Use of sonography to evaluate carotid atherosclerosis in the elderly. The Cardiovascular Health Study. CHS Collaborative Research Group. - O'Leary, D H; Polak, J F; Wolfson, S K; Bond, M G; Bommer, W; Sheth, S; Psaty, B M; Sharrett, A R; Manolio, T A (Stroke, 1991)
Carotid sonography is being performed on more than 5,000 participants in the Cardiovascular Health Study, a prospective, multicenter study of cardiovascular disease in men and women aged 65 years and older. The sonographic methods used to examine and measure the extracranial carotid arteries are described. Initial validation studies were performed on 61 subjects with a mean age of 68.6 years. Analysis of within- and between-sonographer differences and between-reader differences were performed for selected variables. In general, the mean absolute differences for within- and between-sonographer comparisons were small, with even less variability between readers. Variability was less for the common carotid artery than for the internal carotid artery. These data suggest that carotid sonography is a reliable and reproducible method for use in the study of carotid atherosclerosis in population studies.
Keywords: Age Factors; Aged; Arteriosclerosis; Carotid Arteries; Carotid Artery Diseases; Carotid Artery, Internal; Female; Humans; Image Interpretation, Computer-Assisted; Image Processing, Computer-Assisted; Male; Prospective Studies; Ultrasonography

Distribution and correlates of sonographically detected carotid artery disease in the Cardiovascular Health Study. The CHS Collaborative Research Group. - O'Leary, D H; Polak, J F; Kronmal, R A; Kittner, S J; Bond, M G; Wolfson, S K; Bommer, W; Price, T R; Gardin, J M; Savage, P J (Stroke, 1992)
BACKGROUND AND PURPOSE: This article describes the prevalence of extracranial carotid atherosclerosis assessed by ultrasonography, its association with risk factors, and its relation to symptomatic coronary disease and stroke in men and women aged > or = 65 years. METHODS: Maximum percent stenosis, maximum common carotid artery wall thickness, and maximum internal carotid artery wall thickness were assessed using duplex ultrasound in 5,201 men and women aged > or = 65 years in the Cardiovascular Health Study, a study of the risk factors and natural history of cardiovascular disease in the elderly. Existing coronary disease and stroke were assessed by physical examination and participant history. RESULTS: Detectable carotid stenosis was present in 75% of men and 62% of women, although the prevalence of > or = 50% stenosis was low, 7% in men and 5% in women. Maximum stenosis and maximum wall thickness measurements increased with age and were uniformly greater at all ages in men than in women (p < 0.00001). Established risk factors for atherosclerosis (hypertension, smoking, diabetes) and indications of vascular disease (left ventricular hypertrophy, major electrocardiographic abnormality, bruits, and history of heart disease or stroke) related to all three carotid artery measures in the elderly. Of the three ultrasound measures, the best correlate for a history of coronary disease was maximum internal carotid artery wall thickness. For stroke the best correlate was common carotid artery wall thickness. Multiple logistic regression models of prevalent coronary heart disease and stroke that included the ultrasound findings indicated, after adjustment for age and sex, that maximum internal wall thickness and maximum common carotid wall thickness were significant correlates of both. Maximum stenosis did not add significantly to the correlation. CONCLUSIONS: In the elderly the incidence of carotid atherosclerosis was high, although the frequency of severe disease was low. The prevalence and severity of carotid atherosclerosis continued to increase with age even in the late decades of life, and more disease was found in men than in women at all ages. Known risk factors for atherosclerosis continued to relate to carotid abnormalities in the later decades of life, both in symptomatic and asymptomatic subjects.
Keywords: Aged; Arteriosclerosis; Cardiomegaly; Carotid Artery Diseases; Cerebrovascular Disorders; Coronary Disease; Female; Humans; Male; Medical Records; Prevalence; Regression Analysis; Risk Factors; Ultrasonography

Echocardiographic design of a multicenter investigation of free-living elderly subjects: the Cardiovascular Health Study. - Gardin, J M; Wong, N D; Bommer, W; Klopfenstein, H S; Smith, V E; Tabatznik, B; Siscovick, D; Lobodzinski, S; Anton-Culver, H; Manolio, T A (J Am Soc Echocardiogr, 1992)
The Framingham study has shown by M-mode echocardiography that left ventricular hypertrophy is a powerful, independent predictor for the development of coronary heart disease and that increased left atrial dimension has been associated with an increased risk of stroke. No previous population-based study has evaluated the risk factor correlates and predictive value for coronary heart disease and stroke of two-dimensional and Doppler, as well as M-mode, echocardiography. The Cardiovascular Health Study is a multi-year prospective epidemiologic study of 5201 men and women older than 65 recruited from four geographic sites in the United States. The main objectives of incorporating echocardiography were to determine whether echocardiographic indices, or changes in these indices, are (1) correlated with traditional risk factors for coronary heart disease and stroke; and (2) independent predictors of morbidity and mortality for coronary heart disease and stroke. Echocardiographic measurements of interest include those related to global and segmental left ventricular systolic and diastolic structure and function and left atrial size. For each subject, a baseline echocardiogram was recorded in super-VHS tape using a standard protocol and equipment. All studies were sent to a reading center where images were digitized and measurements were made using customized computer algorithms. Calculated data and images were stored on optical disks to facilitate retrieval and future comparisons in longitudinal studies. A second echocardiogram is scheduled in year 7, with a goal of determining whether changes in cardiac anatomy or function over a 5-year period are important predictors of morbidity or mortality from coronary heart disease and stroke. Quality control measures included standardized training of echocardiography technicians and readers, technician observation by a trained echocardiographer, periodic blind duplicate readings with reader review sessions, phantom studies, and quality control adults.
Keywords: Allied Health Personnel; Cerebrovascular Disorders; Coronary Disease; Echocardiography; Echocardiography, Doppler; Humans; Prospective Studies; Quality Control; Risk Factors; United States

Eligibility for cholesterol referral in community-dwelling older adults. The Cardiovascular Health Study. - Manolio, T A; Furberg, C D; Wahl, P W; Tracy, R P; Borhani, N O; Gardin, J M; Fried, L P; O'Leary, D H; Kuller, L H (Ann Intern Med, 1992)
OBJECTIVES: To assess the proportion of community-dwelling adults aged 65 years or older who are eligible for referral for lipoprotein analysis and intervention according to the National Cholesterol Education Program (NCEP) guidelines. DESIGN: Cross-sectional study based on examinations and questionnaires collected in 1989 and 1990. SETTING: Four communities in the U.S. in the Cardiovascular Health Study (CHS), a study of risk factors for heart disease and stroke in older adults. PARTICIPANTS: A sample of 4810 men and women ages 65 to 100 randomly selected and recruited from Health Care Financing Administration Medicare eligibility lists for the four communities; not institutionalized, not wheelchair-bound, not currently receiving therapy for cancer, not currently taking lipid-lowering medications, and not having eaten in the preceding 9 hours. MEASUREMENTS: Total cholesterol and lipoprotein analysis measured in all participants. RESULTS: Total cholesterol levels were less than 5.17 mmol/L (200 mg/dL) in 37% of participants, 5.17 to 6.19 mmol/L (200 to 239 mg/dL) in 39%, and 6.20 mmol/L (240 mg/dL) or greater in 24%. Compared with their counterparts, older participants, especially those over 80 years of age, were more likely to have levels below 5.17 mmol/L, as were men, nonwhites, and those with coronary heart disease or two or more coronary heart disease risk factors (P less than 0.008 for all values). Based on this screening measurement, 2174 participants were eligible for lipoprotein analysis, 80% were eligible for dietary or drug therapy using NCEP guidelines. Overall, 46% of CHS participants were eligible for lipoprotein analysis and 36% for intervention by NCEP guidelines, based on a single cholesterol measurement. CONCLUSION: A substantial proportion of older adults in this community sample were eligible for lipoprotein analysis and intervention. Prospective studies of elderly persons are needed to determine the risk for incident coronary heart disease according to NCEP classifications and the benefits of lipid-lowering treatments in persons in this age group so that intervention strategies may best be targeted to an appropriately high-risk group.
Keywords: Age Factors; Aged; Aged, 80 and over; Cerebrovascular Disorders; Cholesterol, LDL; Coronary Disease; Eligibility Determination; Female; Humans; Hypercholesterolemia; Longitudinal Studies; Male; Primary Prevention; Referral and Consultation; Risk Factors; United States

Lipoprotein lipids in older people. Results from the Cardiovascular Health Study. The CHS Collaborative Research Group. - Ettinger, W H; Wahl, P W; Kuller, L H; Bush, T L; Tracy, R P; Manolio, T A; Borhani, N O; Wong, N D; O'Leary, D H (Circulation, 1992)
BACKGROUND: Cardiovascular disease is the leading cause of death and disability in older people. There is little information about the distributions of risk factors in older populations. This article describes the distribution and correlates of lipoprotein lipids in people greater than or equal to 65 years old. METHODS AND RESULTS: Lipoprotein lipid concentrations were measured in 2,106 men (M) and 2,732 women (F) who were participants in the Cardiovascular Health Study, a population-based epidemiological study. Distributions of lipids by age and sex and bivariate and multivariate relations among lipids and other variables were determined in cross-sectional analyses. Mean concentrations of lipids were cholesterol: M, 5.20 +/- 0.93 mmol/l (201 +/- 36 mg/dl) and F, 5.81 +/- 0.98 mmol/l (225 +/- 38 mg/dl); triglyceride (TG): M, 1.58 +/- 0.85 mmol/l (140 +/- 75 mg/dl) and F, 1.57 +/- 0.78 mmol/l (139 +/- 69 mg/dl); high density lipoprotein cholesterol (HDL-C): M, 1.23 +/- 0.33 mmol/l (48 +/- 16 mg/dl), and F, 1.53 +/- 0.41 mmol/l (59 +/- 16 mg/dl); low density lipoprotein cholesterol (LDL-C): M, 3.27 +/- 0.85 mmol/l (127 +/- 33 mg/dl) and F, 3.57 +/- 0.93 mmol/l (138 +/- 36 mg/dl). The total cholesterol to HDL-C ratios were M, 4.49 +/- 1.29 and F, 4.05 +/- 1.22. TG, total cholesterol, and LDL-C concentrations were lower with increasing age, the last more evident in men than in women. TG concentration was positively associated with obesity (in women), central fat patterning, glucose intolerance, use of beta-blockers (in men), and use of estrogens (in women) and negatively associated with age, renal function, alcohol use, and socioeconomic status. In general, HDL-C had opposite relations with these variables, except that estrogen use was associated with higher HDL-C concentrations. LDL-C concentration was associated with far fewer variables than the other lipids but was negatively associated with age in men and women and positively correlated with obesity and central fat patterning and negatively correlated with renal function and estrogen use in women. There were no differences in total cholesterol and LDL-C concentrations among participants with and without prevalent coronary heart disease and stroke, but TG concentration was higher and HDL-C lower in men with both coronary heart disease and stroke and in women with coronary heart disease. CONCLUSIONS: Cholesterol and cholesterol/HDL-C ratio were lower and HDL-C higher than previously reported values in older people, suggesting that lipid risk profiles may be improving in older Americans. TG and HDL-C concentrations, and to a lesser extent LDL-C, were associated with potentially important modifiable factors such as obesity, glucose intolerance, renal function, and medication use.
Keywords: Aged; Aging; Cardiovascular Diseases; Cardiovascular Physiological Phenomena; Cholesterol, HDL; Cholesterol, LDL; Cross-Sectional Studies; Female; Health Status; Humans; Lipids; Lipoproteins; Male; Multivariate Analysis; Triglycerides

Age-related trends in cardiovascular morbidity and physical functioning in the elderly: the Cardiovascular Health Study. - Bild, D E; Fitzpatrick, A; Fried, L P; Wong, N D; Haan, M N; Lyles, M; Bovill, E; Polak, J F; Schulz, R (J Am Geriatr Soc, 1993)
OBJECTIVE: To describe relationships between age and sub-clinical cardiovascular disease, manifest chronic disease, and physical functioning and limitations among persons aged 65 years and older, with emphasis on the "oldest old," those 85 years and older. DESIGN: Observational population-based study. SETTING: Four U.S. communities: Forsyth County, North Carolina; Sacramento County, California; Washington County, Maryland; and Pittsburgh, Pennsylvania. PARTICIPANTS: 5,201 men and women aged 65 years and older. MEASUREMENTS: Demographic data; histories of cardiovascular disease (CVD), chronic lung disease, arthritis, diabetes, and hypertension; measures of subclinical disease including arm and ankle blood pressures, internal carotid wall thickness and stenosis, ejection fraction, left ventricular mass, fractional shortening, and diastolic function, electrocardiographic left ventricular hypertrophy and cardiac injury score, forced expiratory flow and volume; functional status including self-reported physical functioning, hearing and sight limitations and health status, and performance-based measures of function. These variables were examined among men and women in three age groups: 65-74 years, 75-84 years, and 85 + years. Subgroups of participants with and without manifest CVD were also examined. MAIN RESULTS: In women, the prevalence of CVD and other chronic conditions increased with age, and the highest rates occurred among those 85 years and older. In men, prevalence rates increased between the two younger groups, but the oldest group had lower than expected rates for coronary heart disease, cerebrovascular disease, hypertension, and chronic lung disease. In contrast, there were strong age-related linear trends in most of the subclinical measures of blood pressure, atherosclerosis and pulmonary function and in virtually all measures of functional status in both gender groups across the age range. There was a particularly marked decline in functional status between the two older age groups. While subclinical disease was greater and functional status was poorer among those with manifest CVD, with few exceptions, age-related trends were not significantly different between the two groups. CONCLUSIONS: Lower than expected prevalence rates of CVD among those aged 85 years and older, particularly among men, in this study of community-dwelling elderly may represent selection bias or a real plateauing in disease prevalence with age. However, subclinical disease appears to increase and functional status to decline across the age range in both men and women regardless of the presence of CVD. The apparent increase in subclinical disease with age indicates potential for CVD prevention after age 65.
Keywords: Activities of Daily Living; Age Distribution; Aged; Aged, 80 and over; Cardiovascular Diseases; Female; Humans; Male; Prevalence; Sex Distribution; Socioeconomic Factors

Ankle-arm index as a marker of atherosclerosis in the Cardiovascular Health Study. Cardiovascular Heart Study (CHS) Collaborative Research Group. - Newman, A B; Siscovick, D S; Manolio, T A; Polak, J; Fried, L P; Borhani, N O; Wolfson, S K (Circulation, 1993)
BACKGROUND: Peripheral arterial disease measured noninvasively by the ankle-arm index (AAI) is common in older adults, largely asymptomatic, and associated with clinically manifest cardiovascular disease (CVD). The criteria for an abnormal AAI have varied in previous studies. To determine whether there is an inverse dose-response relation between the AAI and clinical CVD, subclinical disease, and risk factors, we examined the relation of the AAI to cardiovascular risk factors, other noninvasive measures of subclinical atherosclerosis using carotid ultrasound, echocardiography and electrocardiography, and clinical CVD. METHODS AND RESULTS: The AAI was measured in 5084 participants > or = 65 years old at the baseline examination of the Cardiovascular Health Study. All subjects had detailed assessment of prevalent CVD, measures of cardiovascular risk factors, and noninvasive measures of disease. Participants were stratified by baseline clinical CVD status and AAI (< 0.8, > or = 0.8 to < 0.9, > or = 0.9 to < 1.0, > or = 1.0 to < 1.5). Analyses tested for a dose-response relation of the AAI with clinical CVD, risk factors, and subclinical disease. The cumulative frequency of a low AAI was 7.4% of participants < 0.8, 12.4% < 0.9, and 23.6% < 1.0. participants with an AAI < 0.8 were more than twice as likely as those with an AAI of 1.0 to 1.5 to have a history of myocardial infarction, angina, congestive heart failure, stroke, or transient ischemic attack (all P < .01). In participants free of clinical CVD at baseline, the AAI was inversely related to history of hypertension, history of diabetes, and smoking, as well as systolic blood pressure, serum creatinine, fasting glucose, fasting insulin, measures of pulmonary function, and fibrinogen level (all P < .01). Risk factor associations with the AAI were similar in men and women free of CVD except for serum total and low-density lipoprotein cholesterol, which were inversely associated with AAI level only in women. Risk factors associated with an AAI of < 1.0 in multivariate analysis included smoking (odds ratio [OR], 2.55), history of diabetes (OR, 3.84), increasing age (OR, 1.54), and nonwhite race (OR, 2.36). In the 3372 participants free of clinical CVD, other noninvasive measures of subclinical CVD, including carotid stenosis by duplex scanning, segmental wall motion abnormalities by echocardiogram, and major ECG abnormalities were inversely related to the AAI (all P < .01). CONCLUSIONS: There was an inverse dose-response relation of the AAI with CVD risk factors and subclinical and clinical CVD among older adults. The lower the AAI, the greater the increase in CVD risk; however, even those with modest, asymptomatic reductions in the AAI (0.8 to 1.0) appear to be at increased risk of CVD.
Keywords: Aged; Ankle; Arm; Arteriosclerosis; Blood Pressure Determination; Cardiovascular Diseases; Female; Humans; Male; Multivariate Analysis; Peripheral Vascular Diseases; Population Surveillance; Predictive Value of Tests; Risk Factors

Sonographic evaluation of carotid artery atherosclerosis in the elderly: relationship of disease severity to stroke and transient ischemic attack. - Polak, J F; O'Leary, D H; Kronmal, R A; Wolfson, S K; Bond, M G; Tracy, R P; Gardin, J M; Kittner, S J; Price, T R; Savage, P J (Radiology, 1993)
Doppler and real-time ultrasound (US) were performed to evaluate the extent of atherosclerotic changes in the carotid artery and to assess their relationship to prevalent cerebrovascular disease. Real-time US scans and Doppler measurements of the carotid arteries were analyzed in 5,201 subjects aged 65 years or older. Severity of atherosclerotic lesions was associated with increased frequencies of hyperechoic, irregular, and heterogeneous textured lesions (P < .0001). The severity of internal carotid artery stenosis was associated with thickening of the intima-media layer of the common carotid artery wall (r = .37, P < .0001). A history of stroke and transient ischemic attack (TIA) was more likely when hyperechoic, heterogeneous, and irregular lesions were seen in the carotid artery. Internal carotid artery stenosis correlated better with prevalent stroke and TIA than did sonographic descriptions of plaque texture. However, the prevalence of hyperechoic, heterogeneous, and irregular lesions increased as the degree of internal carotid stenosis increased. On real-time images alone, the average of the internal carotid artery maximal wall thickness is the sonographic measure of atherosclerosis that enables the best prediction of prevalent stroke and TIA.
Keywords: Aged; Arteriosclerosis; Carotid Artery Diseases; Carotid Artery, Internal; Carotid Stenosis; Cerebrovascular Disorders; Female; Humans; Ischemic Attack, Transient; Male; Ultrasonography

Correlates of blood pressure in community-dwelling older adults. The Cardiovascular Health Study. Cardiovascular Health Study (CHS) Collaborative Research Group. - Tell, G S; Rutan, G H; Kronmal, R A; Bild, D E; Polak, J F; Wong, N D; Borhani, N O (Hypertension, 1994)
Although elevated blood pressure is an important predictor of cardiovascular disease and stroke in the elderly, little information exists on the distribution and risk factor correlates of blood pressure in this group. As part of the Cardiovascular Health Study, a population-based cohort study of 5201 men and women aged 65 to 101 years, we investigated correlates of systolic and diastolic blood pressure. Multiple regression analyses were conducted for all participants and a subgroup of 2482 without coronary heart disease and not on antihypertensive therapy (the "healthier" subgroup). In the total group, independent predictors of diastolic blood pressure included heart rate, aortic root dimension, creatinine, hematocrit, alcohol use, and black race (positive associations) and internal carotid artery wall thickness, mitral early/late peak flow velocity, white blood cell count, cigarette smoking, and age (negative associations). Positive predictors of systolic blood pressure included mitral late peak flow velocity, left ventricular mass, common carotid artery wall thickness, serum albumin, factor VII, diabetes, alcohol use, and age; negative predictors were coronary heart disease, uric acid, height, and smoking. In the healthier subgroup, positive predictors of diastolic blood pressure included heart rate, hematocrit, serum albumin, creatinine, and body weight, whereas mitral early/late peak flow velocity, serum potassium, smoking, and age inversely related to diastolic pressure. For the same group, common carotid artery wall thickness, left ventricular mass, serum albumin, factor VII, high-density lipoprotein cholesterol, and age were directly related to systolic blood pressure, whereas serum potassium was inversely related. Both systolic and diastolic pressures varied considerably by geographic site.(ABSTRACT TRUNCATED AT 250 WORDS)
Keywords: Aged; Aged, 80 and over; Aging; Blood Pressure; Cohort Studies; Coronary Disease; Female; Health Surveys; Humans; Hypertrophy, Left Ventricular; Male; Regression Analysis; United States

High density lipoprotein cholesterol subfractions in older people. - Ettinger, W H; Verdery, R B; Wahl, P W; Fried, L P (J Gerontol, 1994)
BACKGROUND: High density lipoprotein (HDL) may be an important risk factor for cardiovascular disease in older people. HDL is heterogeneous with several subfractions. This article describes the distribution and correlates of HDL2 cholesterol (C) and HDL3-C in older people. METHODS: HDL subfraction cholesterols were measured in 1,127 females and 825 males > or = 65 years old who participated in the Cardiovascular Health Study. Distributions of HDL subfraction cholesterols and bivariate and multivariate relationships were determined in cross-sectional analyses. RESULTS: Mean (+/- SD) concentrations of HDL subfractions were: HDL3-C (M .98 +/- .25, F 1.2 +/- .29 mmol/l), HDL2-C (M .09 +/- .08, F .13 +/- .09 mmol/l). HDL2-C, but not HDL3-C, was slightly higher with age. Using multivariate analysis, both HDL2-C and HDL3-C (in females) were inversely correlated with triglyceride, body weight, and fasting insulin; HDL3-C was inversely correlated with central fat distribution in women. Both HDL2-C and HDL3-C were lower in participants with prevalent cardiovascular disease. However, only HDL3-C was significantly inversely related to carotid stenosis, as measured by ultrasound. CONCLUSIONS: The slight increase in HDL-C with age appears to be due to an increase in the HDL2-C subfraction. HDL-C subfractions are independently related to triglyceride levels, body weight, and insulin concentrations in older people, all potentially modifiable risk factors. Both HDL2-C and HDL3-C are lower in older people with prevalent cardiovascular disease, although only HDL3-C was correlated with carotid atherosclerosis. These findings are consistent with the hypothesis that HDL subfractions are important risk factors for atherosclerotic cardiovascular disease in the elderly.
Keywords: Aged; Aged, 80 and over; Alcohol Drinking; Body Weight; Carotid Stenosis; Cholesterol; Cholesterol, HDL; Cholesterol, LDL; Cohort Studies; Coronary Disease; Cross-Sectional Studies; Drug Therapy; Female; Humans; Insulin; Lipoproteins, HDL; Lipoproteins, HDL2; Lipoproteins, HDL3; Male; Sex Factors; Socioeconomic Factors

Relation of smoking with carotid artery wall thickness and stenosis in older adults. The Cardiovascular Health Study. The Cardiovascular Health Study (CHS) Collaborative Research Group. - Tell, G S; Polak, J F; Ward, B J; Kittner, S J; Savage, P J; Robbins, J (Circulation, 1994)
BACKGROUND: Cigarette smoking has been associated with increased risk of atherosclerotic diseases in hospital-based studies and in studies of middle-aged populations but not in population-based studies of older adults with and without clinical cardiovascular disease. METHODS AND RESULTS: We investigated the relation of smoking to carotid artery atherosclerotic disease, expressed as intimal-medial wall thickness and arterial lumen narrowing (stenosis) measured by ultrasound. Subjects were 5116 older adults participating in the baseline examination of the Cardiovascular Health Study, a community-based study of cardiovascular diseases in older age. With increased smoking there was significantly greater internal and common carotid wall thickening and internal carotid stenosis: current smokers > former smokers > never-smokers; for instance, the unadjusted percent stenosis was 24%, 20%, and 16%, respectively (P < .0001). A significant dose-response relation was seen with pack-years of smoking. These findings persisted after adjusting for other cardiovascular risk factors and were also confirmed when analyses were restricted to those without prevalent cardiovascular disease. The difference in internal carotid wall thickness between current smokers and nonsmokers was greater than the difference associated with 10 years of age among never-smoking participants (0.39 mm versus 0.31 mm). Among all participants, the prevalence of clinically significant (> or = 50%) internal carotid stenosis increased from 4.4% in never-smokers to 7.3% in former smokers to 9.5% in current smokers (P < .0001). CONCLUSIONS: These findings extend previous reports of a positive relation between smoking and carotid artery disease to a population-based sample of older adults using several different indicators of atherosclerotic disease.
Keywords: Aged; Aged, 80 and over; Carotid Arteries; Carotid Stenosis; Cohort Studies; Female; Humans; Male; Smoking; Ultrasonography

Hematological and biochemical laboratory values in older Cardiovascular Health Study participants. - Robbins, J; Wahl, P; Savage, P; Enright, P; Powe, N; Lyles, M (J Am Geriatr Soc, 1995)
OBJECTIVE: To define reference hematologic and biochemical lab values in older individuals. DESIGN: Randomly selected, age- and gender-stratified participants. SETTING: Visits by participants to four research clinics. PATIENTS: A total of 5201 participants in the Cardiovascular Health Study, an observational study of older Medicare-eligible individuals living at home. MEASUREMENT: Information about health status, previous illness, and medication use was obtained from participants and/or their MDs. This information was used to define a healthy subset of the population. Blood samples were obtained for Cholesterol, HDL and LDL cholesterol, fasting and 2-hour postload glucose and insulin, fibrinogen, factors VII and VIII, potassium, creatinine, albumin, uric acid, white blood count, hematocrit, hemoglobin, and platelet count. RESULTS: Significant differences were found for age group and/or gender for all mean values. Many tests were significantly different from the generally accepted reference ranges used in clinical laboratories. CONCLUSIONS: In some situations accepted laboratory norms for the general population can not be extrapolated to older adults. There are implications for both research and clinical practice.
Keywords: Age Factors; Aged; Analysis of Variance; California; Cardiovascular Diseases; Cohort Studies; Female; Health Status; Humans; Male; Maryland; Middle Aged; North Carolina; Pennsylvania; Reference Values; Risk Factors; Sex Characteristics

Asthma and its association with cardiovascular disease in the elderly. The Cardiovascular Health Study Research Group. - Enright, P L; Ward, B J; Tracy, R P; Lasser, E C (J Asthma, 1996)
Cardiovascular disease (CVD) is more prevalent in elderly than in middle-aged patients. Symptoms such as intermittent wheezing with dyspnea may then be due to either CVD or asthma. The objective of this study was to determine the prevalence and correlates of asthma in the elderly and their associations with CVD and CVD risk factors. A community sample of 5201 elderly persons from the Cardiovascular Health Study was asked if they had a physician diagnosis of asthma, and multiple cardiovascular risk and disease variables were measured. Six percent of the participants (309) recalled a history of asthma, and half of these were never smokers. Thirty percent of those with asthma were currently taking a bronchodilator, 14% inhaled steroids, and 10% oral prednisone. Men and women with asthma who were cigarette smokers were more likely to report a concurrent diagnosis of congestive heart failure than smokers without asthma (p = .04). However, when we determined the independent CVD correlates of asthma in this cohort, controlling for smoking status, age, gender, and diagnoses of chronic bronchitis and emphysema, only higher levels of high-density lipoprotein cholesterol (HDL-C) and higher plasma fibrinogen levels were significantly associated with asthma. It was concluded that asthma is as prevalent in the elderly as in middle-aged persons and is associated with higher HDL-C and higher fibrinogen levels, but not with prevalent cardiovascular disease.
Keywords: Aged; Aged, 80 and over; Asthma; Cardiovascular Diseases; Cohort Studies; Female; Humans; Lung; Male; Multivariate Analysis; Prevalence; Risk Factors; Sex Distribution; Smoking

Hypertension and outcomes research. From clinical trials to clinical epidemiology. - Psaty, B M; Siscovick, D S; Weiss, N S; Koepsell, T D; Rosendaal, F R; Lin, D; Heckbert, S R; Wagner, E H; Furberg, C D (Am J Hypertens, 1996)
Outcomes research seeks to identify effective evidence-based methods of providing the best medical care. While randomized clinical trials (RCT) usually provide the clearest answers, they are often not done or not practicable. More than a decade after the introduction of calcium channel blockers and angiotensin converting enzyme (ACE) inhibitors, clinical trial data about their effect on major disease endpoints in patients with hypertension are still not available. The primary alternatives are the use of randomized trials that include surrogate endpoints, such as level of blood pressure or extent of carotid atherosclerosis, and the use of observational studies that include major disease endpoints. Both approaches, their strengths and limitations, are discussed in detail. The possibility of residual confounding limits the strength of inferences that can be drawn from observational studies. Similarly, the possibility of important drug effects, other than those involving the surrogate endpoint, limits the inferences that can be drawn from randomized trials that rely solely on surrogate outcomes as guides to therapy. In the absence of evidence from large clinical trials that include major disease endpoints, treatment decisions and guidelines need to synthesize the best available information from a variety of sources. Consistency of findings across various study designs, outcomes, and populations is critical to the practice of evidence-based medicine and the effort to maximize the health benefits of antihypertensive therapies.
Keywords: Clinical Trials as Topic; Epidemiologic Methods; Evidence-Based Medicine; Humans; Hypertension; Outcome Assessment (Health Care)

Lipoprotein levels in elderly patients with asthma. Cardiovascular Health Study Research Group. - Enright, P L; Lasser, E C; Ward, B J; Tracy, R P (J Allergy Clin Immunol, 1996)
Keywords: Aged; Aging; Arteriosclerosis; Asthma; Female; Humans; Lipoproteins; Male; Prospective Studies; Risk Factors; Sex Factors

Prevalence and correlates of snoring and observed apneas in 5,201 older adults. - Enright, P L; Newman, A B; Wahl, P W; Manolio, T A; Haponik, E F; Boyle, P J (Sleep, 1996)
The objectives of this study were to describe the prevalence of snoring, observed apneas, and daytime sleepiness in older men and women, and to describe the relationships of these sleep disturbances to health status and cardiovascular diseases (CVD). A cross-sectional design was employed to study sleep problems, CVD, general health, psychosocial factors, and medication use. The subjects were participants in the Cardiovascular Health Study, which included 5,201 adults, aged 65 and older, who were recruited from a random sample of Medicare enrollees in four U.S. communities. Study measures employed were sleep questions, echocardiography, carotid ultrasound, resting electrocardiogram, cognitive function, cardiopulmonary symptoms and diseases, depression, independent activities of daily living (IADLs), and benzodiazepine use. Thirty-three percent of the men and 19% of the women reported loud snoring, which was less frequent in those over age 75. Snoring was positively associated with younger age, marital status, and alcohol use in men, and obesity, diabetes, and arthritis in women. Snoring was not associated, however, with cardiovascular risk factors or clinical CVD in men or women. Observed apneas were reported much less frequently (13% of men and 4% women) than snoring, and they were associated with alcohol use, chronic bronchitis, and marital status in men. Observed apneas were associated with depression and diabetes in women. In both men and women, daytime sleepiness was associated with poor health, advanced age, and IADL limitations. The conclusions of the study were that loud snoring, observed apneas, and daytime sleepiness are not associated cross-sectionally with hypertension or prevalent CVD in elderly persons.
Keywords: Activities of Daily Living; Age Factors; Aged; Cardiovascular Diseases; Comorbidity; Female; Humans; Incidence; Lung Diseases; Male; Narcolepsy; Prevalence; Random Allocation; Sex Factors; Sleep Apnea Syndromes; Snoring

Risk factors for abdominal aortic aneurysms in older adults enrolled in The Cardiovascular Health Study. - Alcorn, H G; Wolfson, S K; Sutton-Tyrrell, K; Kuller, L H; O'Leary, D (Arterioscler Thromb Vasc Biol, 1996)
B-mode ultrasound examinations of the abdominal aorta were performed from 1990 to 1992 to evaluate the prevalence of abdominal aortic aneurysm (AAA) in a subgroup of the Pittsburgh cohort (656 participants, aged 65 to 90 years) of the Cardiovascular Health Study (CHS). In this pilot study, we evaluated various definitions of aneurysm and the reproducibility of the measurements. In year 5 (1992 to 1993) of the CHS, the entire cohort (4741 participants) was examined. AAA was defined as an infrarenal aortic diameter of > or= 3.0 cm, or a ratio of infrarenal to suprarenal diameter of > or= 1.2, or a history of AAA repair. For the entire CHS cohort, prevalence of aneurysms was 9.5% (451/4741) overall, with a prevalence among men of 14.2% (278/1956) and prevalence among women of 6.2% (173/2785). Variables significantly related to AAA were older age; male sex; history of angina, coronary heart disease, and myocardial infarction; lower ankle-arm blood pressure ratio; higher maximum carotid stenosis; greater intima-media thickness of the internal carotid artery; higher creatinine; lower HDL levels and higher LDL levels; and cigarette smoking. The study has documented the strong association of cardiovascular risk factors and measures of clinical and subclinical atherosclerosis and cardiovascular disease and prevalence of aneurysms. We used a definition that is more sensitive than previously reported (diameter or ratio), which allowed the detection of smaller aneurysms and possibly those at an earlier stage of development. Follow-up of this cohort may lead to new criteria for determining the risk factors for progression of aneurysms.
Keywords: Aged; Anthropometry; Aortic Aneurysm, Abdominal; Blood Pressure; Cardiovascular Diseases; Cohort Studies; Comorbidity; Female; Humans; Male; Middle Aged; Pilot Projects; Prevalence; Reproducibility of Results; Risk Factors; Smoking; Ultrasonography; United States

White blood cell counts in persons aged 65 years or more from the Cardiovascular Health Study. Correlations with baseline clinical and demographic characteristics. - Bovill, E G; Bild, D E; Heiss, G; Kuller, L H; Lee, M H; Rock, R; Wahl, P W (Am J Epidemiol, 1996)
A higher white blood cell (WBC) count has been shown to be a risk factor for myocardial infarction and stroke in middle-aged populations. This study evaluated the relation between baseline WBC count and other risk factors, as well as subclinical and prevalent disease, in the Cardiovascular Health Study, an epidemiologic study of coronary heart disease and stroke in 5,201 persons aged 65 years or older. Baseline data were collected over a 12-month period in 1989-1990. WBC counts were statistically significantly higher in people with prevalent and subclinical atherosclerotic cardiovascular disease than in those who were free of disease. WBC counts correlated (p < 0.01) positively with coagulation factors, measures of glucose metabolism, creatinine, smoking, and triglycerides. In contrast, WBC counts correlated negatively with high density lipoprotein cholesterol, forced expiratory volume, forced vital capacity, and height. The correlations between WBC counts and risk factors were similar in both the entire cohort and the subgroup of persons who had never smoked. The authors conclude that WBC counts in the elderly are associated with prevalent and subclinical atherosclerotic cardiovascular disease, as well as its risk factors.
Keywords: Age Distribution; Aged; Aged, 80 and over; Cerebrovascular Disorders; Female; Humans; Leukocyte Count; Leukocytosis; Longitudinal Studies; Male; Myocardial Infarction; Prevalence; Reference Values; Risk Factors; United States

The association of antihypertensive agents with MRI white matter findings and with Modified Mini-Mental State Examination in older adults. - Heckbert, S R; Longstreth, W T; Psaty, B M; Murros, K E; Smith, N L; Newman, A B; Williamson, J D; Bernick, C; Furberg, C D (J Am Geriatr Soc, 1997)
OBJECTIVES: To examine the association of antihypertensive regimen with magnetic resonance imaging (MRI) white matter hyperintensity and with cognitive impairment in older adults. DESIGN: Cross-sectional study. SETTING: The Cardiovascular Health study, an observational prospective cohort study of risk factors for coronary heart disease and stroke in men and women 65 years of age and older. PARTICIPANTS: 1268 men and women with pharmacologically treated hypertension. MEASUREMENTS: Information on medication use, medical history, and health habits was collected at clinic examinations. Participants completed the Modified Mini-Mental State Examination (3MS) and underwent MRI examination. Without clinical information, study neuroradiologists assigned an overall grade of white matter signal intensity on MRI on a scale from 0 (no findings) to 9 (extensive findings). RESULTS: Adjusted mean white matter grade was higher for users of calcium channel blockers (2.59, P = .007) and users of loop diuretics (2.60, P = .015) than for users of beta blockers (2.12). The association was present for both dihydropyridine and non-dihydropyridine calcium channel blockers. Adjusted mean 3MS scores were lower for users of calcium channel blockers (89.6, P < .002), especially dihydropyridines, and users of loop diuretics (89.7, P < .006) than for users of beta blockers (92.3). No statistically significant association could be shown for users of other drug regimens, including thiazides and ACE inhibitors. CONCLUSION: In this study, users of antihypertensive regimens which included calcium channel blockers or loop diuretics had more severe white matter hyperintensity on MRI and worse performance on 3MS than users of beta blockers.
Keywords: Adrenergic beta-Antagonists; Aged; Aged, 80 and over; Antihypertensive Agents; Brain; Calcium Channel Blockers; Cognition; Cohort Studies; Cross-Sectional Studies; Diuretics; Female; Geriatric Assessment; Humans; Magnetic Resonance Imaging; Male; Risk Factors

Diabetes mellitus and echocardiographic left ventricular function in free-living elderly men and women: The Cardiovascular Health Study. - Lee, M; Gardin, J M; Lynch, J C; Smith, V E; Tracy, R P; Savage, P J; Szklo, M; Ward, B J (Am Heart J, 1997)
This report describes the relation among diabetes, blood pressure, and prevalent cardiovascular disease, and echocardiographically measured left ventricular mass and filling (transmitral valve flow) velocities in the Cardiovascular Health Study, a cohort of 5201 men and women > or = 65 years of age. Ventricular septal and left posterior wall thicknesses were greater in diabetic than in nondiabetic subjects, showing a significant linear trend (p = 0.025 for ventricular septal thickness in both sexes combined, p = 0.002 for posterior wall thickness) with increased duration of diabetes. Increased wall thickness of the ventricular septum or the left posterior wall was not associated with prevalent coronary heart disease (CHD) in the cohort. Increased left ventricular mass was associated with diabetic persons not reporting CHD and with all subjects with CHD regardless of glucose tolerance status. After adjusting for body weight, blood pressure, heart rate, and prevalent coronary or cerebrovascular disease, diabetes (as measured by glucose level, insulin use, oral hypoglycemic use, and a positive history of diabetes before baseline examination) remained an independent predictor of increased left ventricular mass among men and women (174.2 gm in diabetic men vs 169.8 gm in normal men, 138.2 gm in diabetic women vs 134.0 gm in normal women, p = 0.043 for both sexes combined). Both early and late diastolic transmitral peak flow velocities were higher with increased duration of diabetes, but the calculated ratio of the early peak flow velocity to the late velocity (E/A ratio) did not differ significantly between subjects with historical diabetes and those with normal fasting glucose (both genders combined, p = 0.190). Glucose level, insulin use, oral hypoglycemic use, and a positive history of diabetes before baseline examination were significant independent predictors of the late transmitral peak flow velocity and its integrated flow-velocity curve but not for the integral of the early peak flow velocity or the E/A ratio. Diabetes is associated with abnormal left ventricular structure and function in elderly persons. This association persists after adjustment for body weight, blood pressure, heart rate, and reported coronary or cerebrovascular disease.
Keywords: Aged; Blood Flow Velocity; Blood Pressure; Diabetes Mellitus; Echocardiography; Female; Glucose Tolerance Test; Humans; Male; Mitral Valve; Residence Characteristics; Ventricular Function, Left

Does the association of risk factors and atherosclerosis change with age? An analysis of the combined ARIC and CHS cohorts. The Atherosclerosis Risk in Communities (ARIC) and Cardiovascular Health Study (CHS) investigators. - Howard, G; Manolio, T A; Burke, G L; Wolfson, S K; O'Leary, D H (Stroke, 1997)
INTRODUCTION: A decrease in the estimated relative risk of cerebrovascular and cardiovascular diseases associated with known disease risk factors has been observed among elderly cohorts, perhaps suggesting that continued risk factor management in the elderly may not be as efficacious as with younger age groups. In this paper, the differential magnitude of the association of risk factors with atherosclerosis across the age spectrum from 45 years to older than 75 years is presented. METHODS: Subclinical atherosclerosis as measured by carotid ultrasonography and risk factor prevalence were assessed using similar methods among participants aged 45 to 64 years in the Atherosclerosis Risk in Communities (ARIC) study and among participants 65 years and older in the Cardiovascular Health Study (CHS). Pooling these two cohorts provided data on the relationship of risk factors and atherosclerosis on nearly 19,000 participants over a broad age range. Regression analyses were used to assess the consistency of the magnitude of the association of risk factors with atherosclerosis across the age spectrum separately for black and white participants in cross-sectional analyses. RESULTS: As expected, each of the risk factors was globally (across all ages) associated with increased atherosclerosis. However, the magnitude of the association did not differ across the age spectrum for hypertension, low density lipoprotein cholesterol (LDL-c), fibrinogen, or body mass index (BMI). For whites, there was a significantly greater impact of smoking and HDL-C among older age strata but a smaller impact of diabetes. For black women, the impact of HDL-C decreased among the older age strata. CONCLUSIONS: These data suggest that most risk factors continue to be associated with increased atherosclerosis at older ages, possibly suggesting a continued value in investigation of strategies to reduce atherosclerosis by controlling risk factors at older ages.
Keywords: African Americans; African Continental Ancestry Group; Aged; Aging; Arteriosclerosis; Body Mass Index; Cardiovascular Physiological Phenomena; Cardiovascular System; Carotid Arteries; Cholesterol, HDL; Cholesterol, LDL; Cohort Studies; European Continental Ancestry Group; Female; Fibrinogen; Health Status; Humans; Hypertension; Male; Middle Aged; Regression Analysis; Risk Factors; Sex Factors; Smoking; Tunica Intima; Tunica Media; Ultrasonography

Health status of individuals with mild stroke. - Duncan, P W; Samsa, G P; Weinberger, M; Goldstein, L B; Bonito, A; Witter, D M; Enarson, C; Matchar, D (Stroke, 1997)
BACKGROUND AND PURPOSE: Diminished quality of life and limitations in higher levels of physical functioning are often underestimated in stroke and are not fully captured by measures such as the Barthel Index and the Rankin Outcome Scale. This study used additional measures to assess the health status of 304 persons with mild stroke and to compare these individuals with 184 persons with transient ischemic attack and 654 persons without history of stroke/transient ischemic attack but at elevated risk for stroke (asymptomatic group). METHODS: Subjects were recruited from the Academic Medical Center Consortium (inpatients), the Cardiovascular Health Study (population-based sample of community-dwelling persons 65 years and older), and United HealthCare (inpatients and outpatients typically younger than 65 years). Subjects were interviewed by telephone or in person to assess activities of daily living (Barthel Index), depression (Center for Epidemiological Studies Depression Scale), health status (MOS-36), and utility for current health state. RESULTS: Most respondents were independent on all Barthel items. The stroke group was more impaired on the MOS-36 than the asymptomatic group but similar to the group with transient ischemic attack. Health-related quality of life was lowest for persons with stroke. While symptom status and Barthel Index score were the strongest predictors of health status, the Barthel Index showed a consistent ceiling effect when compared with the physical function subscale of the MOS-36. CONCLUSIONS: The consequences of even mild stroke affect all dimensions of health except pain. Standardized assessment of persons with stroke must evaluate across the entire continuum of health-related functions.
Keywords: Age Distribution; Aged; Cerebrovascular Disorders; European Continental Ancestry Group; Female; Health Status; Humans; Ischemic Attack, Transient; Male; Middle Aged; Social Support

Incidence of and risk factors for atrial fibrillation in older adults. - Psaty, B M; Manolio, T A; Kuller, L H; Kronmal, R A; Cushman, M; Fried, L P; White, R; Furberg, C D; Rautaharju, P M (Circulation, 1997)
BACKGROUND: This study aimed to describe the incidence of atrial fibrillation (AF) among older adults during 3 years of follow-up. METHODS AND RESULTS: In this cohort study, 5201 adults > or = 65 years old were examined annually on four occasions between June 1989 and May 1993. At baseline, participants answered questionnaires and underwent a detailed examination that included carotid ultrasound, pulmonary function tests, ECG, and echocardiography. Subjects with a pacemaker or AF at baseline (n=357) were excluded. New cases of AF were identified from three sources: (1) annual self-reports, (2) annual ECGs, and (3) hospital discharge diagnoses. Cox proportional-hazards models were used to assess baseline risk factors as predictors of incident AF. Among 4844 participants, 304 developed a first episode of AF during an average follow-up of 3.28 years, for an incidence of 19.2 per 1000 person-years. The onset was strongly associated with age, male sex, and the presence of clinical cardiovascular disease. For men 65 to 74 and 75 to 84 years old, the incidences were 17.6 and 42.7, respectively, and for women, 10.1 and 21.6 events per 1000 person-years. In stepwise models, the use of diuretics, a history of valvular heart disease, coronary disease, advancing age, higher levels of systolic blood pressure, height, glucose, and left atrial size were all associated with an increased risk of AF. The use of beta-blockers and high levels of alcohol use, cholesterol, and forced expiratory volume in 1 second were associated with a reduced risk of AF. CONCLUSIONS: The incidence of AF in older adults may be higher than estimated by previous population studies. Left atrial size appears to be an important risk factor, and the control of blood pressure and glucose may be important in preventing the development of AF.
Keywords: Adult; Aged; Atrial Fibrillation; Blood Glucose; Blood Pressure; Cerebrovascular Disorders; Cohort Studies; Coronary Disease; Electrocardiography; Female; Follow-Up Studies; Hospital Records; Humans; Incidence; Male; Prospective Studies; Risk Factors; United States

Infarctlike lesions in the brain: prevalence and anatomic characteristics at MR imaging of the elderly--data from the Cardiovascular Health Study. - Bryan, R N; Wells, S W; Miller, T J; Elster, A D; Jungreis, C A; Poirier, V C; Lind, B K; Manolio, T A (Radiology, 1997)
PURPOSE: To determine the prevalence and anatomic characteristics of infarctlike lesions seen on cranial magnetic resonance (MR) images. MATERIALS AND METHODS: The study cohort consisted of 5,888 community-living individuals aged 65 years and older enrolled in a longitudinal, population-based study of cardiovascular disease. MR images were obtained from 3,658 participants and evaluated by trained readers. Lesion size, anatomic location, and signal intensity were recorded. Infarctlike lesion was defined as a nonmass, hyperintense region on spin-density- and T2-weighted images and, in cerebral white matter and brain stem, a hypointense region on T1-weighted images. RESULTS: Infarctlike lesions were depicted on MR images of 1,323 (36%) participants. Eighty-five percent (1,128 participants) had lesions 3 mm or larger in maximum dimension, although 70.9% (1,320 of 1,861) of these lesions were 10 mm or less. Lesion prevalence increased with age, especially with lesions 3 mm or larger, which increased from 22.1% (86 of 389) in the 65-69-year age group to 42.9% (88 of 205) in the over-85-year age group (P < .0001). Lesion prevalence was slightly greater in men (497 of 1,527 [32.5%]) than in women (631 of 2,131 [29.6%]), but did not differ between blacks and non-blacks. The deep nuclei were the most commonly affected anatomic sites, with 78.2% (1,451 of 1,856) of lesions. Lesions that involved the cerebrum and posterior fossa accounted for 11.7% (218 of 1,856) and 10.1% (187 of 1,856) of lesions, respectively. CONCLUSION: If the lesions reported in this study indicate cerebrovascular disease, subclinical disease may be more prevalent than clinical disease, and the prevalence of disease may rise with age. Also, infarctlike lesions have a distinctive anatomic profile.
Keywords: Aged; Brain; Cardiovascular Diseases; Cerebral Infarction; Cohort Studies; Female; Humans; Longitudinal Studies; Magnetic Resonance Imaging; Male; Prevalence

Left ventricular mass in the elderly. The Cardiovascular Health Study. - Gardin, J M; Arnold, A; Gottdiener, J S; Wong, N D; Fried, L P; Klopfenstein, H S; O'Leary, D H; Tracy, R; Kronmal, R (Hypertension, 1997)
Left ventricular (LV) mass, as estimated from M-mode echocardiography (echo), has previously been shown to be an independent predictor of incident cardiovascular disease morbidity and mortality. We evaluated the relationship at baseline of echo LV mass to relevant cardiovascular disease risk factors and other potential covariates in the Cardiovascular Health Study, multicenter study sponsored by the National Heart, Lung, and Blood Institute of 5201 men and women aged 65 years or older (mean, 73). Two-dimensionally directed M-mode echo LV mass measurements could be obtained in 1357 men and 2053 women (66% of this elderly cohort). Stepwise linear regression analyses of the relationship of echo LV mass to demographic and risk factor, physical activity, electrocardiographic, and prevalent disease variables resulted in a model that explained 37% of the variance for the entire cohort. In order of decreasing importance, factors positively associated with echo LV mass were body weight, male sex, systolic pressure, presence of congestive heart failure, present smoking, major and minor electrocardiographic abnormalities, treatment for hypertension, valvular heart disease, aortic regurgitation by color Doppler, and mitral regurgitation by color Doppler (in men) whereas diastolic pressure, bioresistance (a measure of adiposity), and high-density lipoprotein cholesterol were inversely related to echo LV mass. Although height and weight were both related to LV mass, height added nothing once weight was entered in multiple linear regression analyses. Furthermore, in the multiple regression models, diastolic pressure was inversely and systolic BP positively related to LV mass, with similar magnitudes for their coefficients. In consonance with these findings, pulse pressure was positively related to LV mass in bivariate analyses. Multiple linear regression analyses explained less of the variance for ventricular septal thickness (R2 = .13) and LV posterior wall thickness (R2 = .14) than for LV mass (R2 = .37) and LV diastolic dimension (R2 = .27). Intriguing findings in the elderly Cardiovascular Health Study cohort included the presence of pulse pressure as a positive correlate, and high-density lipoprotein cholesterol as an inverse correlate, of LV mass. Longitudinal studies in the Cardiovascular Health Study cohort will help to clarify the importance of demographic, risk factor, and other variables, and changes in these variables, in predicting changes in echo LV mass and its components as well as the prognostic significance of LV mass in the elderly.
Keywords: Aged; Aged, 80 and over; Blood Pressure; Body Weight; Cardiovascular Diseases; Cohort Studies; Echocardiography; Female; Humans; Hypertrophy, Left Ventricular; Male; Prospective Studies; Risk Factors; Ventricular Function, Left

Sleep disturbance, psychosocial correlates, and cardiovascular disease in 5201 older adults: the Cardiovascular Health Study. - Newman, A B; Enright, P L; Manolio, T A; Haponik, E F; Wahl, P W (J Am Geriatr Soc, 1997)
OBJECTIVES: To describe the prevalence of self reported sleep disturbances in older men and women and to describe their relationships with health status and cardiovascular disease (CVD). DESIGN: Cross-sectional study of sleep disturbance, CVD, general health, psychosocial factors, physical function, and use of psychotropic medications. SETTING: Participants of the Cardiovascular Health Study, 5201 adults aged 65 and older recruited from a random sample of noninstitutionalized Medicare enrollees in four US communities. MEASURES: Self-reported sleep disturbances and standardized questionnaires for cardiopulmonary symptoms and diseases, depression, social support, activities of daily living, physical activity, cognitive function, and current medications, spirometry, ECG, echocardiography, and carotid ultrasound. RESULTS: Women were twice as likely as men to report difficulty falling asleep (30% vs 14%). Daytime sleepiness, difficulty falling asleep, and frequent awakenings increased in prevalence with age. All symptoms were related strongly to depression. Symptoms of daytime sleepiness were also related strongly to poor health and limitations in activities of daily living in men and women. In multivariate analysis, men taking benzodiazepines were likely to report difficulty falling asleep and daytime sleepiness, whereas women taking benzodiazepines reported difficulty falling asleep and waking up too early. After accounting for these factors, the only cardiovascular disease independently associated with sleep disturbances was angina. Men and women with confirmed angina were 1.6 times more likely to report trouble falling asleep. Independent relationships between sleep disturbances and cardiovascular risk factors such as obesity, hypertension, smoking, and diabetes were relatively weak and inconsistent, though smokers were less likely to report frequent awakenings. CONCLUSIONS: Sleep disturbances are relatively common in older men and women and are associated with poor health, depression, angina, limitations in activities of daily living, and the use of benzodiazepines.
Keywords: Aged; Aged, 80 and over; Cardiovascular Diseases; Cross-Sectional Studies; Depression; Female; Geriatric Assessment; Health Surveys; Humans; Male; Prevalence; Psychotropic Drugs; Random Allocation; Risk Factors; Sex Factors; Sleep Wake Disorders; Social Support; Surveys and Questionnaires; United States

The Sleep Heart Health Study: design, rationale, and methods. - Quan, S F; Howard, B V; Iber, C; Kiley, J P; Nieto, F J; O'Connor, G T; Rapoport, D M; Redline, S; Robbins, J; Samet, J M; Wahl, P W (Sleep, 1997)
The Sleep Heart Health Study (SHHS) is a prospective cohort study designed to investigate obstructive sleep apnea (OSA) and other sleep-disordered breathing (SDB) as risk factors for the development of cardiovascular disease. The study is designed to enroll 6,600 adult participants aged 40 years and older who will undergo a home polysomnogram to assess the presence of OSA and other SDB. Participants in SHHS have been recruited from cohort studies in progress. Therefore, SHHS adds the assessment of OSA to the protocols of these studies and will use already collected data on the principal risk factors for cardiovascular disease as well as follow-up and outcome information pertaining to cardiovascular disease. Parent cohort studies and recruitment targets for these cohorts are the following: Atherosclerosis Risk in Communities Study (1,750 participants), Cardiovascular Health Study (1,350 participants), Framingham Heart Study (1,000 participants), Strong Heart Study (600 participants), New York Hypertension Cohorts (1,000 participants), and Tucson Epidemiologic Study of Airways Obstructive Diseases and the Health and Environment Study (900 participants). As part of the parent study follow-up procedures, participants will be surveyed at periodic intervals for the incidence and recurrence of cardiovascular disease events. The study provides sufficient statistical power for assessing OSA and other SDB as risk factors for major cardiovascular events, including myocardial infarction and stroke.
Keywords: Adult; Aged; Aged, 80 and over; Arteriosclerosis; Cohort Studies; Coronary Disease; Female; Humans; Hypertension; Longitudinal Studies; Male; Middle Aged; Polysomnography; Positive-Pressure Respiration; Prospective Studies; Research Design; Sleep Apnea Syndromes

Use of calcium channel blockers and breast carcinoma risk in postmenopausal women. - Fitzpatrick, A L; Daling, J R; Furberg, C D; Kronmal, R A; Weissfeld, J L (Cancer, 1997)
BACKGROUND: The use of calcium channel blockers in an elderly population recently was reported to be associated with the incidence of cancer. The Cardiovascular Health Study, a multisite observational cohort study, provided the opportunity to investigate the epidemiologic association between the use of calcium channel blockers and breast carcinoma risk in 3198 women age > or = 65 years. METHODS: Standard questionnaires and clinical procedures were administered at four study sites annually from 1989-1990 to 1993-1994. Drug usage was assessed by a medication inventory and hospitalizations for 75 incident invasive breast carcinoma cases were identified using International Classification of Diseases-9 Clinical Modification codes. Time-dependent Cox proportional hazards regression models were used to assess associations between incident breast carcinoma and the use of specific antihypertensive medication including calcium channel blockers. RESULTS: In adjusted Cox proportional hazards models, an elevated risk of breast carcinoma was associated with use of calcium channel blockers (hazard ratio [HR]: 2.57; 95% confidence interval [CI], 1.47-4.49). This association persisted when the comparison group was users of other antihypertensive medication. No associations between the use of other antihypertensive medication with incident breast carcinoma were found. Associations were enhanced by assessment of high dose at baseline (HR: 4.42; 95% CI, 1.37-14.27) and when calcium channel blockers were combined with estrogen use (HR: 4.48; 95% CI, 1.58-12.75). The association was found to be strongest for the use of estrogens with immediate release calcium channel blockers (HR: 8.48; 95% CI, 2.99-24.08). CONCLUSIONS: Although the number of cases was limited in this observational study, associations found between the use of calcium channel blockers and incident invasive breast carcinoma warrant further investigation. Site specific carcinomas should be included as an outcome of ongoing and planned long term clinical trials using calcium channel blockers.
Keywords: Age Factors; Aged; Breast Neoplasms; Calcium Channel Blockers; Cohort Studies; Estrogens; Female; Humans; Postmenopause; Proportional Hazards Models; Risk Factors

Asymptomatic internal carotid artery stenosis defined by ultrasound and the risk of subsequent stroke in the elderly. The Cardiovascular Health Study. - Longstreth, W T; Shemanski, L; Lefkowitz, D; O'Leary, D H; Polak, J F; Wolfson, S K (Stroke, 1998)
BACKGROUND AND PURPOSE: We sought in this study to relate carotid ultrasound findings in asymptomatic older adults to the 5-year risk of various cerebrovascular outcomes used in the Asymptomatic Carotid Atherosclerosis Study (ACAS). METHODS: The Cardiovascular Health Study (CHS) is a longitudinal study of people 65 years and older. Analyses of internal carotid artery stenosis defined by multiple different cutoffs of peak systolic velocity, rather than one particular cutoff, were performed in the 5441 participants who underwent carotid ultrasound and lacked a history of transient ischemic attack or stroke. The 5-year risks of 7 cerebrovascular disease outcomes used in ACAS were estimated for each cutoff. RESULTS: Associations with the 5-year risk of outcomes were substantially elevated only at cutoffs with high peak systolic velocities. In this population, the number of people with such high velocities was small. For example, with a cutoff of approximately 2.5 m/s, suggesting a stenosis of >70%, the 5-year risk of an ipsilateral fatal or nonfatal stroke was 5%, and only 0.5% of the group had velocities at least this high. CONCLUSIONS: In a group of older adults likely to participate in a screening program, as evidenced by willingness to participate in CHS, high peak systolic velocities consistent with high-grade carotid stenosis were uncommon and risk of subsequent cerebrovascular disease outcomes was relatively low. These findings do not suggest that similar populations of older adults would benefit from a program using ultrasound to screen for asymptomatic carotid stenosis.
Keywords: Aged; Blood Flow Velocity; Carotid Artery, Internal; Carotid Stenosis; Cerebrovascular Disorders; Cohort Studies; Female; Humans; Male; Prevalence; Risk Factors; Systole; Ultrasonography, Doppler

A brain image database for structure/function analysis. - Letovsky, S I; Whitehead, S H; Paik, C H; Miller, G A; Gerber, J; Herskovits, E H; Fulton, T K; Bryan, R N (AJNR Am J Neuroradiol, 1998)
BACKGROUND AND PURPOSE: Lesion-deficit-based structure-function analysis has traditionally been empirical and nonquantitative. Our purpose was to establish a new brain image database (BRAID) that allows the statistical correlation of brain functional measures with anatomic lesions revealed by clinical brain images. METHODS: Data on 303 participants in the MR Feasibility Study of the Cardiovascular Health Study were tested for lesion/deficit correlations. Functional data were derived from a limited neurologic examination performed at the time of the MR examination. Image data included 3D lesion descriptions derived from the MR examinations by hand segmentation. MR images were normalized in-plane using local, linear Talairach normalization. A database was implemented to support spatial data structures and associated geometric and statistical operations. The database stored the segmented lesions, patient functional scores, and several anatomic atlases. Lesion-deficit association was sought by contingency testing (chi2-test) for every possible combination of each neurologic variable and each labeled atlas structure. Significant associations that confirmed accepted lesion-deficit relationships were sought. RESULTS: Two-hundred thirty-five infarctlike lesions in 117 subjects were viewed collectively after mapping into Talairach cartesian coordinates. Anatomic structures most strongly correlated with neurologic deficits tended to be situated in anatomically appropriate areas. For example, infarctlike lesions associated with visual field defects were correlated with structures in contralateral occipital structures, including the optic radiations and occipital gyri. CONCLUSION: Known lesion-deficit correlations can be established by a database using a standard coordinate system for representing spatial data and incorporating functional and structural data together with appropriate query mechanisms. Improvements and further applications of this methodology may provide a powerful technique for uncovering new structure-function relationships.
Keywords: Brain; Brain Mapping; Cerebral Infarction; Databases as Topic; Humans; Image Processing, Computer-Assisted; Magnetic Resonance Imaging; Neurologic Examination

Correlates of daytime sleepiness in 4578 elderly persons: the Cardiovascular Health Study. - Whitney, C W; Enright, P L; Newman, A B; Bonekat, W; Foley, D; Quan, S F (Sleep, 1998)
OBJECTIVES: To describe the prevalence of self-reported daytime sleepiness in older men and women and to describe their relationships with demographic factors, nocturnal complaints, health status, and cardiovascular diseases (CVD). DESIGN: Cross-sectional survey and clinical exam. SETTING: Participants in the Cardiovascular Health Study, 4578 adults aged 65 and older, recruited from a random sample of non-institutionalized Medicare enrollees in four U.S. communities. MEASURES: Daytime sleepiness measured by the Epworth Sleepiness Scale (ESS), magnetic resonance imaging of the brain (MRI), cognitive function tests, and standardized questionnaires for cardiopulmonary symptoms and diseases, depressive symptoms, social support, activities of daily living, physical activity, and current medications. RESULTS: Approximately 20% of the participants reported that they were "usually sleepy in the daytime". Although elderly black men were less likely to report frequent awakenings than those in the other three race and gender groups, they had significantly higher mean ESS scores. The following were independently associated with higher ESS scores in gender-specific models: non-white race, depression, loud snoring, awakening with dyspnea or snorting, frequent nocturnal awakenings, medications used to treat congestive heart failure, non-use of sleeping pills, a sedentary lifestyle, and limitation of activities of daily living in both men and women; additional correlates included hip circumference and current smoking in men, and hayfever in women. The following were not independently associated with ESS in the models: age, education, use of wine or beer to aid sleep, use of tricyclic antidepressants, long- or short-acting benzodiazepines, asthma, angina, myocardial infarction, congestive heart failure itself, forced vital capacity, social support, cognitive function, or MRI evidence of global brain atrophy or white matter abnormality. CONCLUSIONS: Daytime sleepiness is common in the elderly, probably due to nocturnal disturbances such as frequent awakenings and snoring. The occasional use of sleeping pills for insomnia is associated with reduced daytime sleepiness in the elderly, while the use of medications for congestive heart failure is associated with daytime sleepiness. Surprisingly, anatomic abnormalities such as evidence of previous strokes and brain atrophy (as seen on brain MRI scans) were not associated with daytime sleepiness in these non-institutionalized elderly persons.
Keywords: Activities of Daily Living; Age Distribution; Aged; Aged, 80 and over; Brain; Cardiovascular Diseases; Circadian Rhythm; Cognition Disorders; Cohort Studies; Continental Population Groups; Cross-Sectional Studies; Disorders of Excessive Somnolence; Electrocardiography; Female; Health Status; Health Surveys; Humans; Magnetic Resonance Imaging; Male; Neuropsychological Tests; Prevalence; Sex Distribution

Diabetes in older adults: comparison of 1997 American Diabetes Association classification of diabetes mellitus with 1985 WHO classification. - Wahl, P W; Savage, P J; Psaty, B M; Orchard, T J; Robbins, J A; Tracy, R P (Lancet, 1998)
BACKGROUND: We aimed to compare the prevalence of abnormal glucose tolerance identified by the 1985 WHO and the 1997 American Diabetes Association (ADA) diagnostic categories based on information collected in the Cardiovascular Health Study, an epidemiological study of elderly people. METHODS: We measured glucose concentrations during fasting and 2 h after a 75 g oral glucose-tolerance test in participants aged 65-100 years in the Cardiovascular Health Study. From a 1989 cohort, we analysed the glucose measurements of 4515 individuals without a previous diagnosis of diabetes and of 262 additional measurements from an African-American cohort recruited in 1992-93. FINDINGS: In the 1989 cohort, the prevalence of untreated diabetes with ADA diagnostic fasting criteria was 7.7% versus a prevalence of 14.8% by the WHO criteria. In the African-American cohort, the prevalence of untreated diabetes was 2.7% with ADA criteria and 11.8% with WHO criteria. 3509 (77.7%) of the 4515 participants in the 1989 cohort had normal glucose concentrations according to ADA fasting criteria, compared with 2401 (53.2%) according to WHO criteria. In the African-American cohort, the corresponding numbers were 239 (91.2%) versus 153 (58.4%). All differences in prevalence of abnormal glucose tolerance between ADA and WHO classifications were significant (p<0.0001). INTERPRETATION: Among elderly individuals, there was a significant difference in the prevalence of diabetes identified by the WHO diagnostic criteria based on oral glucose-tolerance test and the ADA fasting criteria. Consequently, many individuals currently classified as non-diabetic according to ADA criteria would previously have had a diagnosis of diabetes according to WHO criteria. Longitudinal studies are needed to assess the value of the criteria in the identification of individuals at increased risk of diabetes-associated chronic complications.
Keywords: African Americans; Aged; Aged, 80 and over; Cohort Studies; Diabetes Mellitus; Female; Glucose Tolerance Test; Humans; Male; Prevalence; Societies, Medical; World Health Organization

High body fatness, but not low fat-free mass, predicts disability in older men and women: the Cardiovascular Health Study. - Visser, M; Langlois, J; Guralnik, J M; Cauley, J A; Kronmal, R A; Robbins, J; Williamson, J D; Harris, T B (Am J Clin Nutr, 1998)
Using data from the Cardiovascular Health Study, we studied the relation between body composition (fat mass and fat-free mass, assessed by bioelectrical impedance) and self-reported, mobility-related disability (difficulty walking or stair climbing) in 2714 women and 2095 men aged 65-100 y. In a cross-sectional analysis at baseline (1989-1990), disability was reported by 26.5% of the women and 16.9% of the men. A positive association was observed between fat mass and disability. The odds ratio for disability in the highest quintile of fat mass was 3.04 (95% CI: 2.18, 4.25) for women and 2.77 (95% CI: 1.82, 4.23) for men compared with those in the lowest quintile. Low fat-free mass was not associated with a higher prevalence of disability. In a longitudinal analysis among persons not reporting disability at baseline, 20.3% of the women and 14.8% of the men reported disability 3 y later. Fat mass at baseline was predictive of disability 3 y later, with odds ratios of 2.83 (95% CI: 1.80, 4.46) for women and 1.72 (95% CI: 1.03, 2.85) for men in the highest quintile of fat. The increased risk was not explained by age, physical activity, chronic disease, or other potential confounders. Low fat-free mass was not predictive of disability. The results showed that high body fatness is an independent predictor of mobility-related disability in older men and women. These findings suggest that high body fatness in old age should be avoided to decrease the risk of disability.
Keywords: Adipose Tissue; Aged; Aged, 80 and over; Body Composition; Cross-Sectional Studies; Disability Evaluation; Female; Geriatric Assessment; Health Surveys; Humans; Male; Obesity; Predictive Value of Tests; Walking

Predicting future years of healthy life for older adults. - Diehr, P; Patrick, D L; Bild, D E; Burke, G L; Williamson, J D (J Clin Epidemiol, 1998)
Cost-effectiveness studies often need to compare the cost of a program to the lifetime benefits of the program, but estimates of lifetime benefits are not routinely available, especially for older adults. We used data from two large longitudinal studies of older adults (ages 65-100) to estimate transition probabilities from one health state to another, and used those probabilities to estimate the mean additional years of healthy life that an older adult of specified age, sex, and health status would experience. We found, for example, that 65-year-old women in excellent health can expect 16.8 years of healthy life in the future, compared to only 8.5 years for women in poor health. We also provide estimates of discounted years of healthy life and future life expectancy. These estimates may be used to extend the effective length of the study period in cost-effectiveness studies, to examine the impact of chronic diseases or risk factors on years of healthy life, or to investigate the relationship of years of life to years of healthy life. Several applications are described.
Keywords: Aged; Aged, 80 and over; Cost-Benefit Analysis; Female; Forecasting; Health Promotion; Health Status; Humans; Life Expectancy; Life Tables; Male; Probability; Quality-Adjusted Life Years; Sex Factors

Reliability of scoring respiratory disturbance indices and sleep staging. - Whitney, C W; Gottlieb, D J; Redline, S; Norman, R G; Dodge, R R; Shahar, E; Surovec, S; Nieto, F J (Sleep, 1998)
STUDY OBJECTIVES: Unattended, home-based polysomnography (PSG) is increasingly used in both research and clinical settings as an alternative to traditional laboratory-based studies, although the reliability of the scoring of these studies has not been described. The purpose of this study is to describe the reliability of the PSG scoring in the Sleep Heart Health Study (SHHS), a multicenter study of the relation between sleep-disordered breathing measured by unattended, in-home PSG using a portable sleep monitor, and cardiovascular outcomes. DESIGN: The reliability of SHHS scorers was evaluated based on 20 randomly selected studies per scorer, assessing both interscorer and intrascorer reliability. RESULTS: Both inter- and intrascorer comparisons on epoch-by-epoch sleep staging showed excellent reliability (kappa statistics >0.80), with stage 1 having the greatest discrepancies in scoring and stage 3/4 being the most reliably discriminated. The arousal index (number of arousals per hour of sleep) was moderately reliable, with an intraclass correlation (ICC) of 0.54. The scorers were highly reliable on various respiratory disturbance indices (RDIs), which incorporate an associated oxygen desaturation in the definition of respiratory events (2% to 5%) with or without the additional use of associated EEG arousal in the definition of respiratory events (ICC>0.90). When RDI was defined without considering oxygen desaturation or arousals to define respiratory events, the RDI was moderately reliable (ICC=0.74). The additional use of associated EEG arousals, but not oxygen desaturation, in defining respiratory events did little to increase the reliability of the RDI measure (ICC=0.77). CONCLUSIONS: The SHHS achieved a high degree of intrascorer and interscorer reliability for the scoring of sleep stage and RDI in unattended in-home PSG studies.
Keywords: Humans; Polysomnography; Reproducibility of Results; Research Design; Sleep Apnea Syndromes; Sleep Stages

Utilities for major stroke: results from a survey of preferences among persons at increased risk for stroke. - Samsa, G P; Matchar, D B; Goldstein, L; Bonito, A; Duncan, P W; Lipscomb, J; Enarson, C; Witter, D; Venus, P; Paul, J E; Weinberger, M (Am Heart J, 1998)
BACKGROUND: Patient beliefs, values, and preferences are crucial to decisions involving health care. In a large sample of persons at increased risk for stroke, we examined attitudes toward hypothetical major stroke. METHODS AND RESULTS: Respondents were obtained from the Academic Medical Center Consortium (n = 621), the Cardiovascular Health Study (n = 321 ), and United Health Care (n = 319). Preferences were primarily assessed by using the time trade off (TTO). Although major stroke is generally considered an undesirable event (mean TTO = 0.30), responses were varied: although 45% of respondents considered major stroke to be a worse outcome than death, 15% were willing to trade off little or no survival to avoid a major stroke. CONCLUSIONS: Providers should speak directly with patients about beliefs, values, and preferences. Stroke-related interventions, even those with a high price or less than dramatic clinical benefits, are likely to be cost-effective if they prevent an outcome (major stroke) that is so undesirable.
Keywords: Adult; Age Distribution; Aged; Aged, 80 and over; Attitude to Health; Female; Health Status; Humans; Intracranial Embolism and Thrombosis; Male; Middle Aged; Quality of Life; Sex Distribution; Surveys and Questionnaires; United States

Cardiovascular disease in older adults with glucose disorders: comparison of American Diabetes Association criteria for diabetes mellitus with WHO criteria. - Barzilay, J I; Spiekerman, C F; Wahl, P W; Kuller, L H; Cushman, M; Furberg, C D; Dobs, A; Polak, J F; Savage, P J (Lancet, 1999)
BACKGROUND: The new fasting American Diabetes Association (ADA) criteria for the diagnosis of diabetes mellitus rely mainly on fasting blood glucose concentrations and use a lower cut-off value for diagnosis than the WHO criteria. We aimed to assess the sensitivity of these criteria for the detection of cardiovascular disease, the main complication of diabetes mellitus in the elderly. METHODS: We did a cross-sectional and prospective analysis of 4515 participants of the Cardiovascular Health Study, an 8 year longitudinal study designed to identify factors related to the onset and course of cardiovascular disease in adults aged at least 65 years. We calculated the prevalence and incidence of cardiovascular disease for the ADA and WHO criteria. FINDINGS: There was a higher prevalence of cardiovascular disease among individuals with impaired glucose or newly diagnosed diabetes by both criteria than among those with normal glucose concentrations. However, because fewer individuals had abnormal glucose states by the fasting ADA criteria (22.3%) than by the WHO criteria (46.8%), the number of cases of cardiovascular disease attributable to abnormal glucose states was a third of that attributable by the WHO criteria (53 vs 159 cases per 10,000). For the two sets of criteria, the relative risk for incident cardiovascular disease (mean follow-up 5.9 years) was higher in individuals with impaired glucose and newly diagnosed diabetes than in those with normal glucose. Individuals classified as normal by the fasting ADA criteria had a higher absolute number of incident events (455 of 581 events) than those classified as normal by the WHO criteria (269 of 581 events). Fasting ADA criteria were therefore less sensitive than the WHO criteria for predicting cardiovascular disease among individuals with abnormal glucose (sensitivity, 28% vs 54%). INTERPRETATION: The new fasting ADA criteria seem to be less predictive than the WHO criteria for the burden of cardiovascular disease associated with abnormal glucose in the elderly.
Keywords: Age Factors; Aged; Blood Glucose; Cardiovascular Diseases; Cross-Sectional Studies; Diabetes Complications; Diabetes Mellitus; Fasting; Female; Glucose Intolerance; Humans; Longitudinal Studies; Male; Prospective Studies; Risk Factors; Sensitivity and Specificity; Societies, Medical; United States; World Health Organization

Carotid-artery intima and media thickness as a risk factor for myocardial infarction and stroke in older adults. Cardiovascular Health Study Collaborative Research Group. - O'Leary, D H; Polak, J F; Kronmal, R A; Manolio, T A; Burke, G L; Wolfson, S K (N Engl J Med, 1999)
BACKGROUND: The combined thickness of the intima and media of the carotid artery is associated with the prevalence of cardiovascular disease. We studied the associations between the thickness of the carotid-artery intima and media and the incidence of new myocardial infarction or stroke in persons without clinical cardiovascular disease. METHODS: Noninvasive measurements of the intima and media of the common and internal carotid artery were made with high-resolution ultrasonography in 5858 subjects 65 years of age or older. Cardiovascular events (new myocardial infarction or stroke) served as outcome variables in subjects without clinical cardiovascular disease (4476 subjects) over a median follow-up period of 6.2 years. RESULTS: The incidence of cardiovascular events correlated with measurements of carotid-artery intima-media thickness. The relative risk of myocardial infarction or stroke increased with intima-media thickness (P<0.001). The relative risk of myocardial infarction or stroke (adjusted for age and sex) for the quintile with the highest thickness as compared with the lowest quintile was 3.87 (95 percent confidence interval, 2.72 to 5.51). The association between cardiovascular events and intima-media thickness remained significant after adjustment for traditional risk factors, showing increasing risks for each quintile of combined intima-media thickness, from the second quintile (relative risk, 1.54; 95 percent confidence interval, 1.04 to 2.28), to the third (relative risk, 1.84; 95 percent confidence interval, 1.26 to 2.67), fourth (relative risk, 2.01; 95 percent confidence interval, 1.38 to 2.91), and fifth (relative risk, 3.15; 95 percent confidence interval, 2.19 to 4.52). The results of separate analyses of myocardial infarction and stroke paralleled those for the combined end point. CONCLUSIONS: Increases in the thickness of the intima and media of the carotid artery, as measured noninvasively by ultrasonography, are directly associated with an increased risk of myocardial infarction and stroke in older adults without a history of cardiovascular disease.
Keywords: Aged; Carotid Arteries; Cerebrovascular Disorders; Disease-Free Survival; Female; Humans; Incidence; Male; Myocardial Infarction; Proportional Hazards Models; Prospective Studies; Risk Factors; Tunica Intima; Tunica Media; Ultrasonography

Oral anticoagulation in patients with atrial fibrillation: adherence with guidelines in an elderly cohort. - White, R H; McBurnie, M A; Manolio, T; Furberg, C D; Gardin, J M; Kittner, S J; Bovill, E; Knepper, L (Am J Med, 1999)
PURPOSE: To determine adherence with practice guidelines in a population-based cohort of elderly persons aged 70 years or older with atrial fibrillation. SUBJECTS AND METHODS: This was a cross-sectional analysis of a subgroup of participants in the Cardiovascular Health Study, a prospective observational study involving four communities in the United States. Subjects were participants with atrial fibrillation on electrocardiogram at one or more yearly examinations from 1993 to 1995. The outcome measure was self-reported use of warfarin in 1995. RESULTS: In 1995, 172 (4.1%) participants had atrial fibrillation together with information regarding warfarin use and no preexisting indication for its use. Warfarin was used by 63 (37%) of these participants. Of the 109 participants not reporting warfarin use, 92 (84%) had at least one of the clinical risk factors (aside from age) associated with stroke in patients with atrial fibrillation. Among participants not taking warfarin, 47% were taking aspirin. Several characteristics were independently associated with warfarin use, including age [odds ratio (OR) = 0.6 per 5-year increment, 95% CI 0.5-0.9], a modified mini-mental examination score <85 points [OR = 0.3, 95% confidence interval (CI) 0.1-0.9], and among patients without prior stroke, female sex (OR = 0.5, 95% CI 0.2-1.0). CONCLUSIONS: Despite widely publicized practice guidelines to treat patients who have atrial fibrillation with warfarin, most participants who had atrial fibrillation were at high risk for stroke but were not treated with warfarin. More studies are needed to determine why elderly patients with atrial fibrillation are not being treated with warfarin.
Keywords: Administration, Oral; Aged; Anticoagulants; Atrial Fibrillation; Cerebrovascular Disorders; Cross-Sectional Studies; Female; Humans; Logistic Models; Male; Odds Ratio; Practice Guidelines as Topic; Prospective Studies; Risk; Risk Factors; Warfarin

Relation of sleepiness to respiratory disturbance index: the Sleep Heart Health Study. - Gottlieb, D J; Whitney, C W; Bonekat, W H; Iber, C; James, G D; Lebowitz, M; Nieto, F J; Rosenberg, C E (Am J Respir Crit Care Med, 1999)
Obstructive sleep apnea syndrome is a well recognized cause of excessive sleepiness; however, the relation of sleepiness to mild sleep-disordered breathing (SDB), which affects as much as half the adult population, is uncertain. In order to explore this relation, we conducted a cross-sectional cohort study of community-dwelling adults participating in the Sleep Heart Health Study, a longitudinal study of the cardiovascular consequences of SDB. The study sample comprises 886 men and 938 women, with a mean age of 65 (SD 11) yr. Sleepiness was quantified using the Epworth Sleepiness Scale (ESS). Sleep-disordered breathing was quantified by the respiratory disturbance index (RDI), defined as the number of apneas plus hypopneas per hour of sleep, measured during in-home polysomnography. When RDI was categorized into four groups (< 5, 5 to < 15, 15 to < 30, >/= 30), a significantly progressive increase in mean ESS score was seen across all four levels of SDB, from 7.2 (4.3) in subjects with RDI < 5 to 9.3 (4.9) in subjects with RDI >/= 30 (p < 0.001). There was no significant modification of this effect by age, sex, body mass index, or evidence of chronic restriction of sleep time or periodic limb movement disorder. The percentage of subjects with excessive sleepiness, defined as an ESS score >/= 11, increased from 21% in subjects with RDI < 5 to 35% in those with RDI >/= 30 (p < 0. 001). We conclude that SDB is associated with excess sleepiness in community-dwelling, middle-aged and older adults, not limited to those with clinically apparent sleep apnea.
Keywords: Aged; Cardiovascular Diseases; Cross-Sectional Studies; Disorders of Excessive Somnolence; Female; Humans; Male; Middle Aged; Polysomnography; Respiration; Retrospective Studies; Severity of Illness Index; Sleep Apnea Syndromes; Surveys and Questionnaires

Relationships of cerebral MRI findings to ultrasonographic carotid atherosclerosis in older adults : the Cardiovascular Health Study. CHS Collaborative Research Group. - Manolio, T A; Burke, G L; O'Leary, D H; Evans, G; Beauchamp, N; Knepper, L; Ward, B (Arterioscler Thromb Vasc Biol, 1999)
Cerebral magnetic resonance imaging (MRI) has demonstrated a high prevalence of infarct-like lesions, white matter hyperintensities, and evidence of cerebral atrophy in older adults. While these findings are generally believed to be related to ischemia and atherosclerosis, their relationship to atherosclerosis in the carotid arteries remains to be explored. Study subjects were part of the multicenter Cardiovascular Health Study, a cross-sectional study of 3502 women and men >/=65 years of age undergoing cranial MRI and carotid ultrasonography. MRI infarcts were detected in 1068 participants (29.3%) and measurable carotid plaque in 2745 (75.3%). MRI infarcts, ventricular and sulcal widening, and white matter score were strongly associated with carotid intimal-medial thickness (IMT) and stenosis degree after adjustment for age and sex (all P<0. 01). Associations with plaque characteristics were less strong and less consistent; MRI infarcts were weakly associated only with surface irregularity, and ventricular size was weakly associated only with lesion density (both P<0.04). In contrast, sulcal widening was strongly related to plaque characteristics, with scores being higher in those with heterogeneous and irregular plaque (both P<0. 009). Adjustment for other risk factors, and for carotid IMT/stenosis, removed associations of MRI findings with plaque characteristics except for weak relationships remaining between MRI infarcts and surface irregularity and between sulcal score and heterogeneous plaque (both P<0.03). MRI abnormalities show strong and consistent relationships with increasing carotid IMT and stenosis degree but less strong associations with plaque characteristics, especially after adjusting for IMT and stenosis.
Keywords: Aged; Arteriosclerosis; Brain; Cardiovascular System; Carotid Artery Diseases; Cerebral Infarction; Cohort Studies; Cross-Sectional Studies; Echoencephalography; Female; Health Status; Humans; Magnetic Resonance Imaging; Male; Prevalence

Survival versus years of healthy life: which is more powerful as a study outcome? - Diehr, P; Patrick, D L; Burke, G L; Williamson, J (Control Clin Trials, 1999)
Studies of interventions that are intended to improve patients' health are often evaluated with survival as the primary outcome, even when a measure adjusted for quality of survival, such as years of healthy life (YHL), would seem more appropriate. The purpose of this article is to determine whether studies based on survival are more or less powerful than studies based on YHL in clinical trials where either measure might be appropriate. We used data from the Cardiovascular Health Study (CHS) to estimate the sample size that would be needed in studies of 156 different health conditions, for the two outcome measures. The median sample size for a 5-year study was 687 if survival was the endpoint and 484 for YHL. YHL usually required lower sample sizes than survival, although survival was more powerful for some health conditions. We also found that lengthy studies, and studies with many follow-up measures per person, did not have appreciably higher power than less intensive studies. We conclude that clinical investigations in which the goal is to improve health may often be performed more efficiently with YHL rather than survival as the primary outcome measure. Such studies can be short in duration, with relatively few measures per person of health status.
Keywords: Aged; Angina Pectoris; Female; Follow-Up Studies; Health Status; Humans; Life Expectancy; Male; Quality-Adjusted Life Years; Randomized Controlled Trials as Topic; Research Design; Sample Size; Survival Analysis; Time Factors; Treatment Outcome

Temporal trends in the use of anticoagulants among older adults with atrial fibrillation. - Smith, N L; Psaty, B M; Furberg, C D; White, R; Lima, J A; Newman, A B; Manolio, T A (Arch Intern Med, 1999)
BACKGROUND: Several recent randomized clinical trials have demonstrated that warfarin sodium treatment, and to a lesser extent aspirin, reduces risk of stroke and death compared with placebo in persons with atrial fibrillation. Insufficient documentation exists on the extent to which the use of these therapies following trial publications has continued to increase in the elderly with atrial fibrillation. METHODS: We used data from the Cardiovascular Health Study, a study of 5888 community-dwelling adults aged 65 years or older, to determine the prevalence of warfarin and aspirin use in persons with electrocardiogram-identified atrial fibrillation. Electrocardiogram examinations were conducted at baseline from 1989 through 1990, and at 6 subsequent annual examinations through 1995-1996. Medication data were collected by inventory methods at each examination. Temporal change in use of anticoagulants was analyzed by comparing percentage use in 1990 to use in each year through 1996. RESULTS: The use of warfarin increased 4-fold from 13% in 1990 to 50% in 1996 among participants with prevalent atrial fibrillation (P<.001). Daily use of aspirin did not increase over time. Participants younger than 80 years were 4 times more likely to use warfarin in 1996 (P<.001) than those 80 years and older. Use of aspirin did not vary significantly with age. CONCLUSIONS: Warfarin use in community-dwelling elderly persons with electrocardiogram-documented atrial fibrillation increased steadily following the first publication of its treatment benefit, reaching 50% by 1996. In contrast, use of aspirin was unchanged during this same period. Continued efforts to promote appropriate anticoagulation therapy to physicians and their patients may still be needed.
Keywords: Aged; Anticoagulants; Aspirin; Atrial Fibrillation; Cerebrovascular Disorders; Drug Therapy; Electrocardiography; Female; Humans; Incidence; Male; Prevalence; Treatment Outcome; Warfarin

Chlamydia pneumoniae, herpes simplex virus type 1, and cytomegalovirus and incident myocardial infarction and coronary heart disease death in older adults : the Cardiovascular Health Study. - Siscovick, D S; Schwartz, S M; Corey, L; Grayston, J T; Ashley, R; Wang, S P; Psaty, B M; Tracy, R P; Kuller, L H; Kronmal, R A (Circulation, 2000)
BACKGROUND: Whether serological evidence of prior infection with Chlamydia pneumoniae, herpes simplex virus type 1 (HSV-1), and cytomegalovirus (CMV) is associated with myocardial infarction (MI) and coronary heart disease (CHD) death remains a source of controversy. METHODS AND RESULTS: We conducted a nested case-control study among participants in the Cardiovascular Health Study, a cohort study of persons aged >/=65 years. Cases experienced an incident MI and CHD death (n=213). Control subjects were matched to cases by age, sex, clinic, year of enrollment, and month of blood draw (n=405). Serum was analyzed for IgG antibodies to C pneumoniae, HSV-1, and CMV. After adjustment for other risk factors, the risk of MI and CHD death was associated with the presence of IgG antibodies to HSV-1 (odds ratio [OR] 2.0, 95% CI 1.1 to 3.6) but was not associated with the presence of IgG antibodies to either C pneumoniae (OR 1.1, 95% CI 0.7 to 1.8) or CMV (OR 1.2, 95% CI 0.7 to 1.9). Although there was little association with low to moderate C pneumoniae antibody titers (</=1:512), high-titer (1:1024) C pneumoniae antibody was associated with an increased risk (OR 2.2, 95% CI 1.1 to 4.4). CONCLUSIONS: Among older adults, the presence of IgG antibodies to HSV-1 was associated with a 2-fold increase in the risk of incident MI and CHD death. For C pneumoniae, only high-titer IgG antibodies were associated with an increased risk of MI and CHD death. The presence of IgG antibodies to CMV was not associated with risk among the elderly.
Keywords: Adult; Age Factors; Aged; Antibodies, Bacterial; Antibodies, Viral; Case-Control Studies; Chlamydophila pneumoniae; Coronary Disease; Cytomegalovirus; Female; Herpesvirus 1, Human; HIV Antibodies; Humans; Immunoglobulin G; Male; Myocardial Infarction; Risk Factors

Clustering of procoagulation, inflammation, and fibrinolysis variables with metabolic factors in insulin resistance syndrome. - Sakkinen, P A; Wahl, P; Cushman, M; Lewis, M R; Tracy, R P (Am J Epidemiol, 2000)
The known metabolic cardiovascular disease risk factors associated with insulin resistance syndrome (IRS) do not adequately explain the excess cardiovascular disease risk attributed to this syndrome, and abnormalities in hemostatic variables may contribute to this excess risk. Using data from 322 nondiabetic elderly men and women (aged 65-100 years) participating in the Cardiovascular Health Study during 1989-1990, the authors performed factor analysis on 10 metabolic risk factors associated with IRS and 11 procoagulation, inflammation, and fibrinolysis variables to examine the clustering of the metabolic and hemostatic risk markers. Factor analysis of the metabolic variables confirmed four uncorrelated factors: body mass, insulin/glucose, lipids, and blood pressure. Adding the hemostatic variables yielded three new factors interpreted as inflammation, vitamin K-dependent proteins, and procoagulant activity. Plasminogen activator inhibitor-1 clustered with the body mass factor, supporting the hypothesis that obesity is related to impaired fibrinolysis. Fibrinogen clustered with the inflammation summary factor rather than procoagulant activity, supporting the position that fibrinogen principally reflects underlying inflammation rather than procoagulant potential. The authors conclude that should hemostatic variables be shown to contribute to IRS-related cardiovascular disease, apart from plasminogen activator inhibitor-1, they may do so independently of the established metabolic abnormalities.
Keywords: Aged; Aged, 80 and over; Antigens; Blood Coagulation; Cardiovascular Diseases; Cluster Analysis; Factor Analysis, Statistical; Factor VII; Female; Fibrinogen; Fibrinolysis; Humans; Inflammation; Insulin Resistance; Male; Middle Aged; Plasminogen Activator Inhibitor 1; Risk Factors

The association of bone mineral density and depression in an older population. - Robbins, J; Hirsch, C; Whitmer, R; Cauley, J; Harris, T (J Am Geriatr Soc, 2001)
OBJECTIVE: To evaluate the association between bone mineral density (BMD) and measurements of depression in an older population. DESIGN: Population-based, cross-sectional study. SETTING: Study subjects were participants in the Cardiovascular Health Study (CHS), a longitudinal, long-term, follow-up study, at the University of California Davis (Sacramento, California) and the University of Pittsburgh (Pittsburgh, Pennsylvania) clinical centers. PARTICIPANTS: A random sample of 1,566 Medicare enrollees age 65 and older enrolled in the CHS. MEASUREMENTS: Total hip BMD, measured using dual energy x-ray absorptiometry (DEXA), after adjustment for multiple covariates, was compared with depression evaluated with the Center for Epidemiological Studies 10-item Depression Scale (CES-Dm). Risk factors for osteoporosis were compared in depressed and nondepressed participants. Potential correlates were entered into a regression model. Depression scores were compared in normal, osteopenic, and osteoporotic individuals. RESULTS: Sixteen percent of participants were clinically depressed; 9% had BMDs in the osteoporotic range. Mean BMD was 40 mg/cm2 lower in those with clinical depression. High CES-Dm scores were associated with lower BMD (P < .001) when adjusted for body mass index (BMI), age, kilocalories of activity, estrogen use, gender, race, smoking and drinking. When stratified by race, this remained true for all Caucasians (P < .01), all African Americans (P < .05), and when stratified by race and gender the association remained only for all Caucasian women (P < .001). In women and Caucasian men there was an increase in depression scores among individuals with osteoporotic-range BMDs. CONCLUSIONS: A significant association was found between BMD and depressive symptoms after adjustment for osteoporosis risk factors. In Caucasians, depressive symptoms were associated with both osteoporotic and osteopenic levels of BMD. Causality cannot be ascribed, with only one measurement of BMD. We postulate that there may be an unmeasured third factor, such as an endogenous steroid, that is responsible for both low BMD and depression.
Keywords: Absorptiometry, Photon; Aged; Analysis of Variance; Black People; Body Mass Index; Bone Density; Bone Diseases, Metabolic; California; Cross-Sectional Studies; Depression; Energy Metabolism; Exercise; Female; Follow-Up Studies; Fractures, Bone; Humans; Linear Models; Male; Osteoporosis; Pennsylvania; Population Surveillance; Psychiatric Status Rating Scales; Radionuclide Imaging; Risk Factors; Sex Distribution; Single-Blind Method; White People

The association of sleep-disordered breathing and sleep symptoms with quality of life in the Sleep Heart Health Study. - Baldwin, C M; Griffith, K A; Nieto, F J; O'Connor, G T; Walsleben, J A; Redline, S (Sleep, 2001)
This study assessed the extent to which sleep-disordered breathing (SDB), difficulty initiating and maintaining sleep (DIMS), and excessive daytime sleepiness (EDS) were associated with impairment of quality of life (QoL) using the SF-36. Participants (n=5,816; mean age=63 years; 52.5% women) were enrolled in the nation-wide population-based Sleep Heart Health Study (SHHS) implemented to investigate sleep-disordered breathing as a risk factor in the development of cardiovascular disease. Each transformed SF-36 scale was analyzed independently using multiple logistic regression analysis with sleep and other potential confounding variables (e.g., age, ethnicity) included as independent variables. Men (11.6%) were significantly more likely to have SDB compared to women (5.6%), while women (42.4%) were significantly more likely to report DIMS than men (32.5%). Vitality was the sole SF-36 scale to have a linear association with the clinical categories of SDB (mild, moderate, severe SDB). However, individuals with severe SDB indicated significantly poorer QoL on several SF-36 scales. Both DIMS and EDS were strongly associated with reduced QoL even after adjusting for confounding variables for both sexes. Findings suggest 1) mild to moderate SDB is associated with reduced vitality, while severe SDB is more broadly associated with poorer QoL, 2) subjective sleep symptoms are comprehensively associated with poorer QoL, and 3) SF-36 mean score profiles for SDB and sleep symptoms are equivalent to other chronic diseases in the U.S. general population.
Keywords: Adult; Cardiovascular Diseases; Chronic Disease; Circadian Rhythm; Disorders of Excessive Somnolence; Female; Health Status; Humans; Male; Middle Aged; Polysomnography; Population Surveillance; Prevalence; Quality of Life; Risk Factors; Severity of Illness Index; Sleep Apnea Syndromes; United States

Associations of subclinical cardiovascular disease with frailty. - Newman, A B; Gottdiener, J S; McBurnie, M A; Hirsch, C H; Kop, W J; Tracy, R; Walston, J D; Fried, L P (J Gerontol A Biol Sci Med Sci, 2001)
BACKGROUND: Frail health in old age has been conceptualized as a loss of physiologic reserve associated with loss of lean mass, neuroendocrine dysregulation, and immune dysfunction. Little work has been done to define frailty and describe the underlying pathophysiology. METHODS: Frailty status was defined in participants of the Cardiovascular Health Study (CHS), a cohort of 5,201 community-dwelling older adults, based on the presence of three out of five clinical criteria. The five criteria included self-reported weight loss, low grip strength, low energy, slow gait speed, and low physical activity. We examined the spectrum of clinical and subclinical cardiovascular disease in those who were frail (3/5 criteria) or of intermediate frailty status (1 or 2/5 criteria), compared to those who were not frail (0/5). We hypothesized that the severity of frailty would be related to a higher prevalence of reported cardiovascular disease (CVD), as well as to a greater extent of CVD, measured by noninvasive testing. RESULTS: Of 4,735 eligible participants, 2,289 (48%) were not frail, 299 (6%) were frail, and 2.147 (45%) were of intermediate frailty status. Those who were frail were older (77.2 yrs) compared to those who were not frail (71.5 yrs) or intermediate (73.4 yrs) (p < .001). Frailty status was associated with clinical CVD and most strongly with congestive heart failure (odds ratio [OR] = 7.51 (95% confidence interval [CI] = 4.66-12.12). In those without a history of a CVD event (n = 1.259), frailty was associated with many noninvasive measures of CVD. Those with carotid stenosis >75% (adjusted OR = 3.41), ankle-arm index <0.8 (adjusted OR = 3.17) or 0.8-0.9 (adjusted OR = 2.01), major electrocardiography (ECG) abnormalities (adjusted OR = 1.58), greater left ventricular (LV) mass by echocardiography (adjusted OR = 1.16), and higher degree of infarct-like lesions in the brain (adjusted OR = 1.71), were more likely to be frail compared to those who were not frail. The overall associations of each of these noninvasive measures of CVD with frailty level were significant (all p < .05). CONCLUSIONS: Cardiovascular disease was associated with an increased likelihood of frail health. In those with no history of CVD, the extent of underlying cardiovascular disease measured by carotid ultrasound and ankle-arm index, LV hypertrophy by ECG and echocardiography, was related to frailty. Infarct-like lesions in the brain on magnet resonance imaging were related to frailty as well.
Keywords: Aged; Ankle; Arm; Black or African American; Blood Pressure; Brain; Cardiovascular Diseases; Carotid Artery Diseases; Cerebral Infarction; Cerebrovascular Disorders; Cohort Studies; Echocardiography; Electrocardiography; Frail Elderly; Health Status; Heart Failure; Humans; Magnetic Resonance Imaging; United States; Vascular Diseases

Frailty in older adults: evidence for a phenotype. - Fried, L P; Tangen, C M; Walston, J; Newman, A B; Hirsch, C; Gottdiener, J; Seeman, T; Tracy, R; Kop, W J; Burke, G; McBurnie, M A (J Gerontol A Biol Sci Med Sci, 2001)
BACKGROUND: Frailty is considered highly prevalent in old age and to confer high risk for falls, disability, hospitalization, and mortality. Frailty has been considered synonymous with disability, comorbidity, and other characteristics, but it is recognized that it may have a biologic basis and be a distinct clinical syndrome. A standardized definition has not yet been established. METHODS: To develop and operationalize a phenotype of frailty in older adults and assess concurrent and predictive validity, the study used data from the Cardiovascular Health Study. Participants were 5,317 men and women 65 years and older (4,735 from an original cohort recruited in 1989-90 and 582 from an African American cohort recruited in 1992-93). Both cohorts received almost identical baseline evaluations and 7 and 4 years of follow-up, respectively, with annual examinations and surveillance for outcomes including incident disease, hospitalization, falls, disability, and mortality. RESULTS: Frailty was defined as a clinical syndrome in which three or more of the following criteria were present: unintentional weight loss (10 lbs in past year), self-reported exhaustion, weakness (grip strength), slow walking speed, and low physical activity. The overall prevalence of frailty in this community-dwelling population was 6.9%; it increased with age and was greater in women than men. Four-year incidence was 7.2%. Frailty was associated with being African American, having lower education and income, poorer health, and having higher rates of comorbid chronic diseases and disability. There was overlap, but not concordance, in the cooccurrence of frailty, comorbidity, and disability. This frailty phenotype was independently predictive (over 3 years) of incident falls, worsening mobility or ADL disability, hospitalization, and death, with hazard ratios ranging from 1.82 to 4.46, unadjusted, and 1.29-2.24, adjusted for a number of health, disease, and social characteristics predictive of 5-year mortality. Intermediate frailty status, as indicated by the presence of one or two criteria, showed intermediate risk of these outcomes as well as increased risk of becoming frail over 3-4 years of follow-up (odds ratios for incident frailty = 4.51 unadjusted and 2.63 adjusted for covariates, compared to those with no frailty criteria at baseline). CONCLUSIONS: This study provides a potential standardized definition for frailty in community-dwelling older adults and offers concurrent and predictive validity for the definition. It also finds that there is an intermediate stage identifying those at high risk of frailty. Finally, it provides evidence that frailty is not synonymous with either comorbidity or disability, but comorbidity is an etiologic risk factor for, and disability is an outcome of, frailty. This provides a potential basis for clinical assessment for those who are frail or at risk, and for future research to develop interventions for frailty based on a standardized ascertainment of frailty.
Keywords: Aged; Aged, 80 and over; Cohort Studies; Disabled Persons; Fatigue; Female; Frail Elderly; Humans; Incidence; Male; Muscle Weakness; Phenotype; Prevalence; Sex Distribution; United States; Weight Loss

Hypertension, heart rate, use of antihypertensives, and incident prostate cancer. - Fitzpatrick, A L; Daling, J R; Furberg, C D; Kronmal, R A; Weissfeld, J L (Ann Epidemiol, 2001)
PURPOSE: Recent studies have reported conflicting results on a possible relationship between hypertension, heart rate, and prostate cancer. A model has been developed suggesting that high blood pressure and high heart rate may both be markers for increased central sympathetic nervous activity, which may result in androgen-mediated stimulation of prostate cancer growth. METHODS: In this study we examined the associations between hypertension, heart rate, use of antihypertensive medications, and incident prostate cancer in a cohort of 2442 men. Data from the Cardiovascular Health Study (CHS), an NHLBI-sponsored observational study of adults age 65 or older in four U.S. communities, were analyzed using Cox proportional hazards regression. Seated systolic and diastolic blood pressures were measured using a standardized protocol at the initial clinical examination and annually at follow-up visits. Medications data were transcribed by trained interviewers from prescription medication containers brought into the clinic by participants. RESULTS: A total of 209 cases of incident prostate cancer were identified from either an ICD-9 code of 185 in hospital medical records (n = 130) or by self-report from annual surveillance interviews (n = 79). An average of 5.6 years of follow-up was available for analyses. No associations between blood pressure measures at entry into the study and prostate cancer were found, although these results may have been affected by subsequent treatment of hypertension. An association between resting heart rate (HR) equal to or greater than 80 beats per minute and incident prostate cancer was found compared to men with a rate of less than 60 beats per minute (HR: 1.6, 95% confidence interval [CI]: 1.03-2.5). An inverse association was found between risk of incident prostate cancer and use of any antihypertensive medication (HR: 0.7, 95% CI: 0.5-0.9). A test of heterogeneity found no difference between use of the specific classes of antihypertensive medication and the association with prostate cancer risk. CONCLUSIONS: These data tend to support the hypothesized causal pathway between vascular disease markers and prostate cancer.
Keywords: Aged; Antihypertensive Agents; Cohort Studies; Heart Rate; Humans; Hypertension; Incidence; Male; Proportional Hazards Models; Prostatic Neoplasms; Risk; United States

M-mode echocardiographic predictors of six- to seven-year incidence of coronary heart disease, stroke, congestive heart failure, and mortality in an elderly cohort (the Cardiovascular Health Study). - Gardin, J M; McClelland, R; Kitzman, D; Lima, J A; Bommer, W; Klopfenstein, H S; Wong, N D; Smith, V E; Gottdiener, J (Am J Cardiol, 2001)
Previous studies have identified a number of echocardiographic variables that predict cardiovascular disease (CVD) events and mortality, but have not focused on a large elderly cohort. The purpose of this study was to determine whether M-mode echocardiographic variables predicted all-cause mortality, incident coronary heart disease (CHD), congestive heart failure (CHF), and stroke in a large prospective, multicenter, population-based study. In the Cardiovascular Health Study, a biracial cohort of 5,888 men and women (mean age 73 years) underwent 2-dimensional M-mode echocardiographic measurements of left ventricular (LV) internal dimensions, wall thickness, mass and geometry, as well as measurement of left atrial dimension and assessment for mitral annular calcium. Participants were followed for 6 to 7 years for incident events; analyses excluded subjects with prevalent disease. One or more echocardiographic measurements were independent predictors of all-cause mortality and incident CHD, CHF, and stroke. After adjustment for anthropometric and traditional CVD risk factors, LV mass was significantly related to incident CHD, CHF, and stroke. The highest quartile of LV mass conferred a hazards ratio of 3.36, compared with the lowest quartile, for incident CHF. Furthermore, incident CHF-free survival was significantly lower for participants with LV mass in the highest versus the 2 lowest quartiles (86% vs 97%, respectively, at 2,500 days). Eccentric and concentric LV hypertrophy, respectively, conferred adjusted hazards ratios, compared with normal LV geometry, of 2.05 and 1.61 for incident CHD, and 2.95 and 3.32 for incident CHF. Thus, in an elderly biracial population, selected 2-dimensional M-mode echocardiographic measurements were important markers of subclinical disease and conferred independent prognostic information for incident CVD events, especially CHF and CHD.
Keywords: Aged; Aged, 80 and over; Analysis of Variance; Coronary Disease; Echocardiography, Doppler; Female; Heart Failure; Humans; Incidence; Male; Predictive Value of Tests; Proportional Hazards Models; Prospective Studies; Risk Factors; Stroke

Patterns of self-rated health in older adults before and after sentinel health events. - Diehr, P; Williamson, J; Patrick, D L; Bild, D E; Burke, G L (J Am Geriatr Soc, 2001)
OBJECTIVES: To describe and compare patterns of change in self-rated health for older adults before death and before and after stroke, myocardial infarction, congestive heart failure, cardiac procedure, hospital admission for cancer, and hip fracture. DESIGN: "Event cohort," measuring time in months before and after the event. SETTING: Four U.S. communities. PARTICIPANTS: 5888 participants in the Cardiovascular Health Study (CHS), sampled from Medicare rolls and followed up to 8 years. Mean age at baseline was 73. MEASUREMENTS: Self-rated health, including a category for death, assessed at 6-month intervals, and ascertainment of events. METHODS: We examined the percentage that was healthy each month in the 5 years before death and in the 2 years before and after the other events, and compared the patterns to a "no event" group and to one another, using graphs and linear regression. RESULTS: For people who died, health status declined slowly until about 9 months before death, when it dropped steeply. Comparing persons equally far from death, health was unrelated to age, but men and whites were healthier than women and blacks. Health for other events declined before the event, dropped steeply at the event, showed some recovery, and then declined further after the event. About 65% to 80% of the subjects were healthy 2 years before their event, but only 35% to 65% were healthy two years afterwards. Patterns were similar although less extreme for the "no event" group. CONCLUSION: Visualizing trajectories of health helps us understand how serious health events changes health. Conclusions about change must be drawn with care because of a variety of possible biases. We have described the trajectories in detail. Work is now needed to explain, predict, and possibly prevent such changes in health.
Keywords: Aged; Cardiovascular Diseases; Cohort Studies; Death; Female; Follow-Up Studies; Health Status; Health Status Indicators; Hip Fractures; Hospitalization; Humans; Linear Models; Longitudinal Studies; Male; Random Allocation; Time Factors

Sleep-disordered breathing and cardiovascular disease: cross-sectional results of the Sleep Heart Health Study. - Shahar, E; Whitney, C W; Redline, S; Lee, E T; Newman, A B; Nieto, F J; O'Connor, G T; Boland, L L; Schwartz, J E; Samet, J M (Am J Respir Crit Care Med, 2001)
Disordered breathing during sleep is associated with acute, unfavorable effects on cardiovascular physiology, but few studies have examined its postulated association with cardiovascular disease (CVD). We examined the cross-sectional association between sleep- disordered breathing and self-reported CVD in 6,424 free-living individuals who underwent overnight, unattended polysomnography at home. Sleep-disordered breathing was quantified by the apnea-hypopnea index (AHI)-the average number of apneas and hypopneas per hour of sleep. Mild to moderate disordered breathing during sleep was highly prevalent in the sample (median AHI: 4.4; interquartile range: 1.3 to 11.0). A total of 1,023 participants (16%) reported at least one manifestation of CVD (myocardial infarction, angina, coronary revascularization procedure, heart failure, or stroke). The multivariable-adjusted relative odds (95% CI) of prevalent CVD for the second, third, and fourth quartiles of the AHI (versus the first) were 0.98 (0.77-1.24), 1.28 (1.02-1.61), and 1.42 (1.13-1.78), respectively. Sleep-disordered breathing was associated more strongly with self-reported heart failure and stroke than with self-reported coronary heart disease: the relative odds (95% CI) of heart failure, stroke, and coronary heart disease (upper versus lower AHI quartile) were 2.38 (1.22-4.62), 1.58 (1.02- 2.46), and 1.27 (0.99-1.62), respectively. These findings are compatible with modest to moderate effects of sleep-disordered breathing on heterogeneous manifestations of CVD within a range of AHI values that are considered normal or only mildly elevated.
Keywords: Aged; Cardiovascular Diseases; Cohort Studies; Cross-Sectional Studies; Female; Humans; Male; Middle Aged; Sleep Apnea Syndromes

The aging and dying processes and the health of older adults. - Diehr, Paula; Williamson, Jeff; Burke, Gregory L; Psaty, Bruce M (J Clin Epidemiol, 2002)
It is difficult to distinguish changes in health due to aging from those related to dying, because the two processes are highly related. Some potentially treatable conditions may mistakenly be dismissed as due to old age. The goal of this article was to examine the relationships of aging and of dying to changes in 10 health-related variables: self-rated health, depression, ADLs, IADLs, minimental state examination, body mass index, blocks walked per week, bed days, hospitalization, and walking speed (all coded so that higher values were better). We used longitudinal data from the Cardiovascular Health Study to estimate the changes in the variables associated with 5 years of aging and also in the 5 years before death, controlling for years from death and for age, respectively. All 10 health variables declined as death approached, and most of them also declined with age. The "effect" of the dying process was usually significantly larger than the effect of aging. Large declines in these health measures are probably not due to aging, and should be taken seriously by patients and their providers.
Keywords: Aged; Aging; Death; Female; Health Status Indicators; Humans; Linear Models; Longitudinal Studies; Male; Muscular Atrophy

Frailty and activation of the inflammation and coagulation systems with and without clinical comorbidities: results from the Cardiovascular Health Study. - Walston, Jeremy; McBurnie, Mary Ann; Newman, Anne; Tracy, Russell P; Kop, Willem J; Hirsch, Calvin H; Gottdiener, John; Fried, Linda P (Arch Intern Med, 2002)
BACKGROUND: The biological basis of frailty has been difficult to establish owing to the lack of a standard definition, its complexity, and its frequent coexistence with illness. OBJECTIVE: To establish the biological correlates of frailty in the presence and absence of concurrent cardiovascular disease and diabetes mellitus. METHODS: Participants were 4735 community-dwelling adults 65 years and older. Frail, intermediate, and nonfrail subjects were identified by a validated screening tool and exclusion criteria. Bivariate relationships between frailty level and physiological measures were evaluated by Pearson chi2 tests for categorical variables and analysis of variance F tests for continuous variables. Multinomial logistic regression was performed to evaluate multivariable relationships between frailty status and physiological measures. RESULTS: Of 4735 Cardiovascular Health Study participants, 299 (6.3%) were identified as frail, 2147 (45.3%) as intermediate, and 2289 (48.3%) as not frail. Frail vs nonfrail participants had increased mean +/- SD levels of C-reactive protein (5.5 +/- 9.8 vs 2.7 +/- 4.0 mg/L), factor VIII (13 790 +/- 4480 vs 11 860 +/- 3460 mg/dL), and, in a smaller subset, D dimer (647 +/- 1033 vs 224 +/- 258 ng/mL) (P< or =.001 for all, chi2 test for trend). These differences persisted when individuals with cardiovascular disease and diabetes were excluded and after adjustment for age, sex, and race. CONCLUSIONS: These findings support the hypothesis that there is a specific physiological basis to the geriatric syndrome of frailty that is characterized in part by increased inflammation and elevated markers of blood clotting and that these physiological differences persist when those with diabetes and cardiovascular disease are excluded.
Keywords: Aged; Aged, 80 and over; Blood Coagulation Disorders; Cardiovascular Diseases; Cohort Studies; Diabetes Complications; Diabetes Mellitus; Female; Frail Elderly; Geriatric Assessment; Humans; Inflammation; Longitudinal Studies; Male

Inflammation and coagulation factors in persons > 65 years of age with symptoms of depression but without evidence of myocardial ischemia. - Kop, Willem J; Gottdiener, John S; Tangen, Catherine M; Fried, Linda P; McBurnie, Mary Ann; Walston, Jeremy; Newman, Anne; Hirsch, Calvin; Tracy, Russell P (Am J Cardiol, 2002)
Depression is associated with increased cardiovascular disease, but the underlying mechanisms are not well understood. This study examines associations of depressive symptoms with inflammation and coagulation factors in persons aged > 65 years. Blood samples were obtained from 4,268 subjects free of cardiovascular disease (age 72.4 +/- 5.5 years, 2,623 women). Inflammation markers were C-reactive protein (CRP), white blood cell (WBC) count, total platelet count, and albumin; coagulation factors included factors VIIc and VIIIc and fibrinogen. Depression was assessed with the Center for Epidemiologic Studies Depression scale, and states of energy depletion with a validated exhaustion index. Statistical adjustments were made for risk factors (age, sex, race, systolic blood pressure, smoking status, diabetes mellitus) and physical measures of frailty (isometric handgrip, timed 15-feet walk test, activity level). Depression was associated with elevated CRP (3.31 +/- 0.10 vs 3.51 +/- 0.21 mg/L), WBC (6.14 +/- 0.03 vs 6.43 +/- 0.11 10(6)/L), fibrinogen (319 +/- 1 vs 326 +/- 3 mg/dl), and factor VIIc (124.6 +/- 0.6% vs 127.2 +/- 1.3%; all p <0.05). Exhaustion also was related to elevated inflammation and coagulation markers (p < 0.05). Exhausted men had markedly elevated CRP levels (6.82 +/- 2.10 mg/L) versus nonexhausted men (3.05 +/- 0.16: p = 0.007). After adjustment for control variables, exhaustion remained associated with albumin (p = 0.033), fibrinogen (p = 0.017), CRP (p = 0.066), and WBC (p = 0.060), whereas associations of depressive symptoms with biochemistry measures lost statistical significance. Thus, depression and exhaustion are associated with low-grade inflammation and elevated coagulation factors in persons aged > 65 years.
Keywords: Aged; Blood Chemical Analysis; Blood Coagulation Factors; Cardiovascular Diseases; Depression; Female; Humans; Inflammation; Male; Risk Factors

Predictors of sleep-disordered breathing in community-dwelling adults: the Sleep Heart Health Study. - Young, Terry; Shahar, Eyal; Nieto, F Javier; Redline, Susan; Newman, Anne B; Gottlieb, Daniel J; Walsleben, Joyce A; Finn, Laurel; Enright, Paul; Samet, Jonathan M (Arch Intern Med, 2002)
BACKGROUND: Sleep-disordered breathing (SDB) is common, but largely undiagnosed in the general population. Information on demographic patterns of SDB occurrence and its predictive factors in the general population is needed to target high-risk groups that may benefit from diagnosis. METHODS: The sample comprised 5615 community-dwelling men and women aged between 40 and 98 years who were enrolled in the Sleep Heart Health Study. Data were collected by questionnaire, clinical examinations, and in-home polysomnography. Sleep-disordered breathing status was based on the average number of apnea and hypopnea episodes per hour of sleep (apnea-hypopnea index [AHI]). We used multiple logistic regression modeling to estimate cross-sectional associations of selected participant characteristics with SDB defined by an AHI of 15 or greater. RESULTS: Male sex, age, body mass index, neck girth, snoring, and repeated breathing pause frequency were independent, significant correlates of an AHI of 15 or greater. People reporting habitual snoring, loud snoring, and frequent breathing pauses were 3 to 4 times more likely to have an AHI of 15 or greater vs an AHI less than 15, but there were weaker associations for other factors with an AHI of 15 or greater. The odds ratios (95% confidence interval) for an AHI of 15 or greater vs an AHI less than 15 were 1.6 and 1.5, respectively, for 1-SD increments in body mass index and neck girth. As age increased, the magnitude of associations for SDB and body habitus, snoring, and breathing pauses decreased. CONCLUSIONS: A significant proportion of occult SDB in the general population would be missed if screening or case finding were based solely on increased body habitus or male sex. Breathing pauses and obesity may be particularly insensitive for identifying SDB in older people. A better understanding of predictive factors for SDB, particularly in older adults, is needed.
Keywords: Adult; Age Factors; Aged; Aged, 80 and over; Cohort Studies; Continental Population Groups; Female; Humans; Male; Middle Aged; Obesity; Predictive Value of Tests; Residence Characteristics; Risk Factors; Sex Factors; Sleep Apnea Syndromes; Snoring

Protein C, antithrombin, and venous thromboembolism incidence: a prospective population-based study. - Folsom, Aaron R; Aleksic, Nena; Wang, Lu; Cushman, Mary; Wu, Kenneth K; White, Richard H (Arterioscler Thromb Vasc Biol, 2002)
Although deficiencies of protein C and antithrombin, 2 natural plasma anticoagulants, are known risk factors for venous thrombosis, population-based prospective incidence data on these associations are lacking. Venous thromboembolic events have been identified in adults in 2 longitudinal cohort studies, the Atherosclerosis Risk in Communities (ARIC) Study and the Cardiovascular Health Study (CHS). Incidence was examined in relation to prediagnostic plasma levels of protein C (ARIC Study only) and antithrombin. Over a mean of 8.1 years of follow-up, there were 130 incident venous thromboembolic events that were not due to cancer in the ARIC Study. The age-adjusted incidence was elevated 3.36-fold (95% CI 1.24 to 9.11) in the 1.1% of subjects with protein C values <2.0 mg/L compared with subjects with higher values. In contrast, in the ARIC Study and the CHS, there was no association between low plasma antithrombin and venous thromboembolism. In conclusion, in this population-based study, a low protein C, but not antithrombin, level has been determined to be associated with an increased incidence of venous thromboembolism. Attributable risk estimates suggest that low protein C levels account for approximately 2.5% of venous thromboembolic events in the ARIC population.
Keywords: Adult; Aged; Aged, 80 and over; Antithrombins; Arteriosclerosis; Cohort Studies; Humans; Incidence; Longitudinal Studies; Middle Aged; Odds Ratio; Population Surveillance; Prospective Studies; Protein C; Protein C Deficiency; Pulmonary Embolism; Thromboembolism; Venous Thrombosis

Racial differences in coronary artery calcification in older adults. - Newman, Anne B; Naydeck, Barbara L; Whittle, Jeff; Sutton-Tyrrell, Kim; Edmundowicz, Daniel; Kuller, Lewis H (Arterioscler Thromb Vasc Biol, 2002)
Reports on race-related differences in coronary artery calcium (CAC) are just beginning to emerge and have not been well studied in the elderly. This study was undertaken to assess whether such differences exist and the relationship between CAC and cardiovascular risk factors in a cohort of elderly community-dwelling adults. CAC was measured by using electron-beam tomography in 614 adults (aged 67 to 99 years), of whom 59% were women and 23% were black. The median CAC score was lower in blacks than in whites for men (159 versus 787, respectively; P<0.001) and for women (134 versus 233, respectively; P=0.02) after adjustment for age, cardiovascular disease, and risk factors for cardiovascular disease, although this difference was stronger and remained significant among men only. Lower CAC scores were also observed in the subgroup of blacks with a history of myocardial infarction. The lower CAC scores in blacks compared with whites observed in this study is consistent with either a lower prevalence of coronary artery disease or a lower extent of calcification of coronary artery disease.
Keywords: Age Factors; Aged; Calcinosis; Cohort Studies; Coronary Artery Disease; Female; Humans; Logistic Models; Male; Risk Factors; Sex Factors; Tomography, X-Ray Computed

Retinal microvascular abnormalities and blood pressure in older people: the Cardiovascular Health Study. - Wong, T Y; Hubbard, L D; Klein, R; Marino, E K; Kronmal, R; Sharrett, A R; Siscovick, D S; Burke, G; Tielsch, J M (Br J Ophthalmol, 2002)
AIM: To examine the relation between blood pressure and retinal microvascular abnormalities in older people. METHODS: The Cardiovascular Health Study is a prospective cohort study conducted in four US communities initiated in 1989 to 1990. Blood pressure was measured according to standardised protocols at each examination. During the 1997-8 examination, retinal photographs were taken of 2405 people aged 69-97 years (2056 without diabetes and 349 with diabetes). Signs of focal microvascular abnormalities (focal arteriolar narrowing, arteriovenous nicking, and retinopathy) were evaluated from photographs according to standardised methods. To quantify generalised arteriolar narrowing, the photographs were digitised and diameters of individual arterioles were measured and summarised. RESULTS: In non-diabetic people, elevated concurrent blood pressure taken at the time of retinal photography was strongly associated with presence of all retinal microvascular lesions. The multivariable adjusted odds ratios, comparing the highest to lowest quintile of concurrent systolic blood pressure, were 4.0 (95% confidence intervals (CI): 2.4 to 6.9, p test of trend<0.001) for focal arteriolar narrowing, 2.9 (95% CI: 1.6 to 5.3, p<0.001) for arteriovenous nicking, 2.8 (95% CI: 1.5 to 5.2, p<0.001) for retinopathy, and 2.1 (95% CI: 1.4 to 3.1, p<0.001) for generalised arteriolar narrowing. Generalised arteriolar narrowing and possibly arteriovenous nicking were also significantly associated with past blood pressure measured up to 8 years before retinal photography, even after adjustment for concurrent blood pressure. These associations were somewhat weaker in people with diabetes. CONCLUSIONS: Retinal microvascular abnormalities are related to elevated concurrent blood pressure in older people. Additionally, generalised retinal arteriolar narrowing and possibly arteriovenous nicking are related to previously elevated blood pressure, independent of concurrent blood pressure. These data suggest that retinal microvascular changes reflect severity and duration of hypertension.
Keywords: Aged; Aged, 80 and over; Blood Pressure; Cohort Studies; Diabetic Retinopathy; Eye; Female; Humans; Male; Microcirculation; Prospective Studies; Retina; Retinal Diseases

Time trends in high blood pressure control and the use of antihypertensive medications in older adults: the Cardiovascular Health Study. - Psaty, Bruce M; Manolio, Teri A; Smith, Nicholas L; Heckbert, Susan R; Gottdiener, John S; Burke, Gregory L; Weissfeld, Joel; Enright, Paul; Lumley, Thomas; Powe, Neil; Furberg, Curt D (Arch Intern Med, 2002)
BACKGROUND: Control of high blood pressure (BP) in older adults is an important part of public health efforts at prevention. OBJECTIVE: To assess recent time trends in the awareness, treatment, and control of high BP and in the use of medications to treat high BP. METHODS: In the Cardiovascular Health Study, 5888 adults 65 years and older were recruited from 4 US centers. At baseline, participants underwent an extensive examination that included the measurement of BP, use of medications, and other risk factors. Participants were followed up with annual visits that assessed BP and medication use from baseline in 1989-1990 through the examination in 1998-1999. The primary outcome measures were control of BP to levels lower than than 140/90 mm Hg and the prevalence of use of various classes of antihypertensive medications. RESULTS: The awareness, treatment, and control of high BP improved during the 1990s. The proportions aware and treated were higher among blacks than whites, though control prevalences were similar. For both groups combined, the control of high BP to lower than 140/90 mm Hg increased from 37% at baseline to 49% in 1999. The 51% whose BP was not controlled generally had isolated mild to moderate elevations in systolic BP. Among treated persons, the improvement in control was achieved in part by a mean increase of 0.2 antihypertensive medications per person over the course of 9 years. Improved control was also achieved by increasing the proportion of the entire Cardiovascular Health Study population that was treated for hypertension, from 34.5% in 1990 to 51.1% in 1999. Time trends in antihypertensive drug use were pronounced. Among those without coronary disease, the use of low-dose diuretics and beta-blockers decreased, while the use of newer agents, such as calcium channel blockers, angiotensin-converting enzyme inhibitors, and alpha-blockers increased. CONCLUSIONS: While control of high BP improved in the 1990s, about half the participants with hypertension had uncontrolled BP, primarily mild to moderate elevations in systolic BP. Low-dose diuretics and beta-blockers--the preferred agents since 1993 according to the recommendations of the Joint National Committee on the Detection, Evaluation and Treatment of High Blood Pressure--remained underused. More widespread use of these agents will be an important intervention to prevent the devastating complications of hypertension, including stroke, myocardial infarction, and heart failure.
Keywords: Age Factors; Aged; Antihypertensive Agents; Awareness; Cohort Studies; Drug Therapy; Female; Health Knowledge, Attitudes, Practice; Humans; Hypertension; Male; Prospective Studies; Time Factors

Diabetes and sleep disturbances: findings from the Sleep Heart Health Study. - Resnick, Helaine E; Redline, Susan; Shahar, Eyal; Gilpin, Adele; Newman, Anne; Walter, Robert; Ewy, Gordon A; Howard, Barbara V; Punjabi, Naresh M (Diabetes Care, 2003)
OBJECTIVE: To test the hypothesis that diabetes is independently associated with sleep-disordered breathing (SDB), and in particular that diabetes is associated with sleep abnormalities of a central, rather than obstructive, nature. RESEARCH DESIGN AND METHODS: Using baseline data from the Sleep Heart Health Study (SHHS), we related diabetes to 1). the respiratory disturbance index (RDI; number of apneas plus hypopneas per h of sleep); 2). obstructive apnea index (OAI; >or=3 apneas/h of sleep associated with obstruction of the upper airway); 3). percent of sleep time < 90% O(2) saturation; 4). central apnea index (CAI; >or=3 apneas [without respiratory effort]/h sleep); 5). occurrence of a periodic breathing (Cheyne Stokes) pattern; and 6) sleep stages. Initial analyses excluding persons with prevalent cardiovascular disease (CVD) were repeated including these participants. RESULTS: Of the 5874 participants included in this report, 692 (11.8%) reported diabetes or were taking oral hypoglycemic medications or insulin and 1002 had prevalent CVD. Among the 4872 persons without CVD, 470 (9.6%) had diabetes. Diabetic participants had worse CVD risk factor profiles than their nondiabetic counterparts, including higher BMI, waist and neck circumferences, triglycerides, higher prevalence of hypertension, and lower HDL cholesterol (P < 0.001, all). Descriptive analyses indicated differences between diabetic and nondiabetic participants in RDI, sleep stages, sleep time <90% O(2) saturation, CAI, and periodic breathing (P < 0.05, all). However, multivariable regression analyses that adjusted for age, sex, BMI, race, and neck circumference eliminated these differences for all sleep measures except percent time in rapid eye movement (REM) sleep (19.0% among diabetic vs. 20.1% among nondiabetic subjects, P < 0.001) and prevalence of periodic breathing (odds ratio [OR] for diabetic subjects versus nondiabetic subjects 1.80, 95% CI 1.02-3.15). Additionally, adjusted analyses showed diabetes was associated with nonstatistically significant elevations in the odds of an increased central breathing index (OR 1.42, 95% CI 0.80-2.55). Addition to the analysis of the 1002 persons with prevalent CVD (including 222 people with diabetes) did not materially change these results. CONCLUSIONS: These data suggest that diabetes is associated with periodic breathing, a respiratory abnormality associated with abnormalities in the central control of ventilation. Some sleep disturbances may result from diabetes through the deleterious effects of diabetes on central control of respiration. The high prevalence of SDB in diabetes, although largely explained by obesity and other confounders, suggests the presence of a potentially treatable risk factor for CVD in the diabetic population.
Keywords: Aged; Diabetes Mellitus; Female; Humans; Logistic Models; Male; Middle Aged; Multivariate Analysis; Prevalence; Risk Factors; Sleep Apnea Syndromes; Sleep Apnea, Obstructive

Fibrin fragment D-dimer and the risk of future venous thrombosis. - Cushman, Mary; Folsom, Aaron R; Wang, Lu; Aleksic, Nena; Rosamond, Wayne D; Tracy, Russell P; Heckbert, Susan R (Blood, 2003)
Plasma D-dimer concentration rises more than 100-fold during acute deep vein thrombosis, but there are no prospective data concerning D-dimer as a risk factor for incident venous thrombosis in a general population. Incident venous thrombosis was ascertained in 2 prospective observational studies, the Atherosclerosis Risk in Communities Study and the Cardiovascular Health Study. Of 21 690 participants enrolled between 1987 and 1993, after 8 years of follow-up, D-dimer was measured using baseline stored plasma of 307 participants who developed venous thrombosis and 616 who did not. Relative to the first quintile of the distribution of D-dimer, the age-adjusted odds ratios for future venous thrombosis for the second to fifth quintiles of D-dimer were 1.6, 2.3, 2.3, and 4.2, respectively (P for trend <.0001). Following added adjustment for sex, race, body mass index, factor V Leiden, prothrombin 20210A, and elevated factor VIII coagulant activity (factor VIII:c), these odds ratios were 1.5, 2.1, 1.9, and 3.0, respectively (P for trend <.0001). Among those with idiopathic thrombosis or secondary thrombosis unrelated to cancer, the adjusted fifth quintile odds ratios were 3.5 and 4.8, respectively. By contrast, D-dimer in the fifth versus first quintile was not related to occurrence of cancer-associated thrombosis (odds ratio, 1.1). Odds ratios for elevated D-dimer were consistently elevated in subgroups defined by age, sex, race, duration of follow-up, and thrombosis type (deep vein thrombosis or pulmonary embolus). D-dimer is strongly and positively related to the occurrence of future venous thrombosis.
Keywords: Aged; Body Mass Index; Cohort Studies; Continental Population Groups; Factor V; Factor VIII; Female; Fibrin Fibrinogen Degradation Products; Humans; Longitudinal Studies; Male; Middle Aged; Odds Ratio; Prospective Studies; Prothrombin; Risk Factors; Venous Thrombosis

Perceptions and implications of received spousal care: evidence from the Caregiver Health Effects Study. - Martire, Lynn M; Schulz, Richard; Wrosch, Carsten; Newsom, Jason T (Psychol Aging, 2003)
The experiences of older care recipients have received far less theoretical and empirical attention than those of their family caregivers. In this study of 91 care recipients, the authors assessed perceptions of the amount, timing, and manner of spousal assistance; the amount of strain experienced from receiving care; and psychological well-being. Although female care recipients were more likely to report dissatisfaction with the manner in which assistance was provided, there were few gender differences in perceptions of care overall. In a stringent test of the hypothesis that perceived quality of spousal care affects recipient well-being, the authors found that poorer quality of care was related to increased depressive symptoms and a decreased sense of mastery 1 year later. These longitudinal effects were independent of the recipient's physical disability, marital quality, and care-receiving strain as well as the caregiver's well-being. These findings argue for a comprehensive assessment of the care-receiving experience that includes both care-recipient and caregiver perspectives.
Keywords: Aged; Caregivers; Chronic Disease; Disabled Persons; Family Health; Female; Health Status; Humans; Longitudinal Studies; Male; Mental Health; Quality of Health Care; Research Design; Spouses

The prevalence and risk factors of retinal microvascular abnormalities in older persons: The Cardiovascular Health Study. - Wong, Tien Yin; Klein, Ronald; Sharrett, A Richey; Manolio, Teri A; Hubbard, Larry D; Marino, Emily K; Kuller, Lewis; Burke, Gregory; Tracy, Russell P; Polak, Joseph F; Gottdiener, John S; Siscovick, David S (Ophthalmology, 2003)
PURPOSE: To describe the prevalence of retinal microvascular characteristics and their associations with atherosclerosis in elderly, nondiabetic persons. DESIGN AND PARTICIPANTS: Population-based, cross-sectional study comprising 2050 men and women aged 69 to 97 years without diabetes, living in four communities. METHODS: Participants underwent retinal photography and standardized grading of retinal microvascular characteristics, including retinopathy (e.g., microaneurysms, retinal hemorrhages), focal arteriolar narrowing, and arteriovenous nicking. In addition, calibers of retinal arterioles and venules were measured on digitized photographs to obtain an estimate of generalized arteriolar narrowing. Atherosclerosis and its risk factors were obtained from clinical examination and laboratory investigations. MAIN OUTCOME MEASURES: Prevalence of retinal microvascular abnormalities and their associations with measures of atherosclerosis. RESULTS: The prevalence of retinal microvascular abnormalities was 8.3% for retinopathy, 9.6% for focal arteriolar narrowing, and 7.7% for arteriovenous nicking. All retinal lesions were associated with hypertension (odds ratios [OR] were 1.8 for retinopathy, 2.1 for focal arteriolar narrowing, 1.5 for arteriovenous nicking, and 1.7 for generalized arteriolar narrowing). After controlling for age, gender, race, mean arterial blood pressure, and antihypertensive medication use, retinopathy was associated with prevalent coronary heart disease (OR, 1.7), prevalent myocardial infarction (OR, 1.7), prevalent stroke (OR, 2.0), presence of carotid artery plaque (OR, 1.9), and increased intima-media thickness of the common carotid (OR, 2.3; fourth vs. first quartile) and internal carotid (OR, 1.8; fourth vs. first quartile) arteries. In contrast, focal arteriolar narrowing, arteriovenous nicking, and generalized arteriolar narrowing were not associated with any measures of atherosclerosis. CONCLUSIONS: Retinal microvascular abnormalities are common in older persons without diabetes and are related to hypertension. Retinopathy is associated with prevalent coronary heart disease, stroke, and carotid artery thickening, but focal and generalized arteriolar narrowing and arteriovenous nicking are not related to most measures of atherosclerosis. These data suggest that retinal microvascular abnormalities reflect processes associated with hypertension but distinct from atherosclerosis.
Keywords: Aged; Aged, 80 and over; Blood Pressure; Coronary Artery Disease; Cross-Sectional Studies; Female; Humans; Hypertension; Male; Prevalence; Retinal Diseases; Retinal Vessels; Risk Factors; United States

Prospective study of the A455V polymorphism in the thrombomodulin gene, plasma thrombomodulin, and incidence of venous thromboembolism: the LITE Study. - Aleksic, N; Folsom, A R; Cushman, M; Heckbert, S R; Tsai, M Y; Wu, K K (J Thromb Haemost, 2003)
Plasma thrombomodulin (soluble TM; sTM) is considered to be a marker of endothelial injury, but a recent report indicated that the relationship of sTM with thrombosis is complex. Venous thromboembolic events were identified in adults in two longitudinal cohort studies, the Atherosclerosis Risk in Communities Study and the Cardiovascular Health Study, totaling 21 690 participants. After 8 years of follow-up, sTM was measured in baseline plasma of 305 participants who developed venous thrombosis and 607 who did not. Thrombomodulin A455V genotype was determined in 302 cases and 626 controls. There was no difference in the prevalence of the three TM genotypes between cases and controls and no difference in age-adjusted mean values of sTM by genotype. There were no associations of age-adjusted sTM or TMA455V genotype with overall venous thromboembolism or with thrombosis in any subtype of venous thromboembolism.
Keywords: Age Factors; Aged; Amino Acid Substitution; Case-Control Studies; Female; Genotype; Humans; Incidence; Male; Polymorphism, Genetic; Prevalence; Prospective Studies; Risk Factors; Thromboembolism; Thrombomodulin; Venous Thrombosis

Variation in symptoms of sleep-disordered breathing with race and ethnicity: the Sleep Heart Health Study. - O'Connor, George T; Lind, Bonnie K; Lee, Elisa T; Nieto, F Javier; Redline, Susan; Samet, Jonathan M; Boland, Lori L; Walsleben, Joyce A; Foster, Gregory L (Sleep, 2003)
STUDY OBJECTIVES: To examine the relation of sleep-related symptoms to race and ethnicity in a diverse sample of middle-aged and older men and women. DESIGN: Cross-sectional questionnaire survey. SETTING: In the initial phase of the Sleep Heart Health Study, men and women enrolled in participating epidemiologic cohort studies were surveyed. PARTICIPANTS: 13,194 men and women 40 years of age and older, including 11,517 non-Hispanic white, 648 black, 643 American Indian, 296 Hispanic, and 90 Asian-Pacific Islander. INTERVENTIONS: Not applicable. MEASUREMENTS AND RESULTS: After adjustment for BMI and other factors, frequent snoring was more common among Hispanic women (odds ratio (OR) = 2.25, 95% confidence interval (CI) = 1.48, 3.42) and black women (OR = 1.55, 95% Ci = 1.13, 2.13) than among non-Hispanic white women. Hispanic men were significantly more likely to report frequent snoring than non-Hispanic white men (OR = 2.30, 95% CI = 1.43, 3.69). Black, American Indian, and Asian men did not differ significantly from white men in snoring prevalence. American Indian women were significantly more likely to report breathing pauses during sleep than their white, non-Hispanic counterparts (OR = 1.52, 95% CI 1.03, 2.24), although polysomnography data on a subset of the sample suggested that the association between this symptom reported on questionnaire and objective evidence of sleep-disordered breathing may be weaker among American Indians than among other groups. Mean Epworth Sleepiness Scale scores were slightly higher in black men and women than in their white, non-hispanic counterparts. CONCLUSIONS: Frequent snoring was more common among black and Hispanic women and Hispanic men than among their white non-Hispanic counterparts, even after adjusting for BMI and other factors. Further research including polysomnography and objective measurements of sleepiness is needed to assess the physiologic and clinical significance of these findings.
Keywords: Adult; Cross-Sectional Studies; Electroencephalography; Electrooculography; Ethnic Groups; Female; Heart Rate; Humans; Male; Polysomnography; Severity of Illness Index; Sleep Apnea Syndromes; Snoring; Surveys and Questionnaires

The Cardiovascular Health Study: a national treasure of cardiovascular information about the elderly. - Wenger, Nanette K; Weber, Michael A; Scheidt, Stephen (Am J Geriatr Cardiol, 2004)
Keywords: Aged; Cardiovascular Diseases; Geriatric Assessment; Humans; Risk Factors

Deep vein thrombosis and pulmonary embolism in two cohorts: the longitudinal investigation of thromboembolism etiology. - Cushman, Mary; Tsai, Albert W; White, Richard H; Heckbert, Susan R; Rosamond, Wayne D; Enright, Paul; Folsom, Aaron R (Am J Med, 2004)
PURPOSE: To determine the incidence of deep vein thrombosis and pulmonary embolism in two cohorts representing regions of the United States. METHODS: The sample comprised 21,680 participants of the Atherosclerosis Risk in Communities study and the Cardiovascular Health Study. Subjects were aged >/=45 years, resided in six communities, and were followed for 7.6 years. All hospitalizations were identified and thromboses were validated by chart review. RESULTS: The age-standardized incidence of first-time venous thromboembolism was 1.92 per 1000 person-years. Rates were higher in men than women, and increased with age in both sexes. There was no antecedent trauma, surgery, immobilization, or diagnosis of cancer for 48% (175/366) of events. The 28-day case-fatality rate was 11% (29/265) after a first venous thromboembolism and 25% (17/67) for cancer-associated thrombosis. The recurrence rate 2 years after a first venous thromboembolism was 7.7% per year (95% confidence interval [CI]: 4.5% to 10.9% per year). Cancer was the only factor independently associated with 28-day fatality (relative risk [RR] = 5.2; 95% CI: 1.4 to 19.9) or recurrent thrombosis (RR = 9.2; 95% CI: 2.0 to 41.7). CONCLUSION: The incidence of venous thromboembolism in this cohort of middle- and older-aged subjects was similar to that observed in more geographically homogeneous samples. Half of cases were idiopathic. Short-term mortality and 2-year recurrence rates were appreciable, especially among subjects with cancer. Based on this study we estimate that 187,000 cases of first-time venous thromboembolism are diagnosed yearly in the United States among those aged 45 years or older.
Keywords: Aged; Case-Control Studies; Cohort Studies; Female; Follow-Up Studies; Humans; Incidence; Male; Middle Aged; Neoplasms; Population Surveillance; Pulmonary Embolism; Recurrence; Risk Factors; Survival Rate; Venous Thrombosis

Mesenteric artery disease in the elderly. - Hansen, Kimberley J; Wilson, David B; Craven, Timothy E; Pearce, Jeffrey D; English, William P; Edwards, Matthew S; Ayerdi, Juan; Burke, Gregory L (J Vasc Surg, 2004)
PURPOSE: The purpose of this study was to estimate the population-based prevalence of mesenteric artery stenosis (MAS) and occlusion among independent elderly Americans. METHOD: As part of an ancillary investigation to the Cardiovascular Health Study (CHS), participants in the Forsyth County, NC cohort had visceral duplex sonography of the celiac arteries and superior mesenteric arteries (SMAs). Critical MAS was defined by celiac peak systolic velocity >or=2.0 m/s and/or SMA peak systolic velocity >or=2.7 m/s. Occlusion of either vessel was defined by lack of a Doppler-shifted signal within the imaged artery. Demographic data, blood pressures, and blood lipid levels were collected as part of the baseline CHS examination. Participants' weights were measured at baseline and before the duplex exam. Univariate tests of association were performed with two-way contingency tables, Student t tests, and Fisher exact tests. Multivariate associations were examined with logistic regression analysis. RESULTS: A total of 553 CHS participants had visceral duplex sonography technically adequate to define the presence or absence of MAS. The study group had a mean age of 77.2 +/- 4.9 years and comprised 63% women and 37% men. Participant race was 76% white and 23% African-American. Ninety-seven participants (17.5%) had MAS. There was no significant difference in age, race, gender, body mass index, blood pressure, cholesterol, or low-density lipoproteins for participants with or without MAS. Forward stepwise variable selection found renal artery stenosis (P =.008; odds ratio [OR], 2.85; 95% confidence interval [CI], 1.31, 6.21) and high-density lipoprotein >40 (P =.02; OR, 3.03; 95% CI, 1.17, 7.81) significantly associated with MAS in a multivariate logistic regression model. Eighty-three of the 97 participants with MAS (15.0% of the cohort) had isolated celiac stenosis. Seven participants (1.3% of the cohort) had combined celiac and SMA stenosis. Five participants (0.9% of the cohort) had isolated SMA stenosis. Two participants (0.4% of the cohort) had celiac occlusion. Considering all participants with MAS, there was no association with weight change. However, SMA stenosis and celiac occlusion demonstrated an independent association with annualized weight loss (P =.028; OR, 1.54; 95% CI, 1.05, 2.26) and with renal artery stenosis (P =.001; OR, 9.48; 95% CI, 2.62, 34.47). CONCLUSION: This investigation provides the first population-based estimate of the prevalence of MAS among independent elderly Americans. MAS existed in 17.5% of the study cohort. The majority had isolated celiac disease. SMA stenosis and celiac artery occlusion demonstrated a significant and independent association with weight loss and concurrent renal artery disease.
Keywords: Age Factors; Aged; Aged, 80 and over; Arteriosclerosis; Celiac Artery; Cohort Studies; Female; Humans; Male; Mesenteric Arteries; Mesenteric Artery, Superior; Mesenteric Vascular Occlusion; Prevalence; Ultrasonography, Doppler, Duplex; Weight Loss

Progressive cognitive impairment after stroke. - Toole, James F; Bhadelia, Rafeeque; Williamson, Jeff D; Veltkamp, Roland (J Stroke Cerebrovasc Dis, 2004)
OBJECTIVE: We examined the putative relationship between stroke and cognitive function in the population-based prospective cohort of the Cardiovascular Health Study (CHS). METHODS: Of the 5888 participants of the CHS aged 65 years or older, there were 5364 with more than one modified mini-mental (3MS) examination between 1992 and 1998. To determine the effect of baseline stroke before first and subsequent (stroke between two consecutive examinations) 3MS examination on cognitive function, linear regression models were computed with potential confounders entered as additional independent variables. Stroke was divided into right and left hemispheres or posterior circulation on the basis of the clinical and/or imaging information by the hospital that treated the event and subsequent adjudication by CHS committee. RESULTS: Participants with baseline stroke had an average 3MS decline of 1.2 (95% confidence interval [CI]: -0.7 - -1.7) points per year more than those without one. Those with a history of subsequent stroke had an average first year 3MS decline of 6.2 (CI -8.7 - -3.7) for left hemisphere, 3.5 (CI -5.3 - -1.8) for right hemisphere, and 1.1 (CI -3.9 - 1.6) for posterior circulation more than those without stroke. The effect of stroke on the rate of cognitive decline appeared to ameliorate after the first year (test for linear trend among those with stroke, P = .003). CONCLUSION: Results from this prospective population-based data study show that stroke in the left hemisphere results in a more pronounced decline in cognition than that in the right hemisphere and that cognitive loss because of stroke appears to attenuate over time, perhaps as a result of relearning.

Sleep and reported daytime sleepiness in normal subjects: the Sleep Heart Health Study. - Walsleben, Joyce A; Kapur, Vishesh K; Newman, Anne B; Shahar, Eyal; Bootzin, Richard R; Rosenberg, Carl E; O'Connor, George; Nieto, F Javier (Sleep, 2004)
STUDY OBJECTIVES: To describe the distribution of nocturnal sleep characteristics and reports of daytime sleepiness in a large well-defined group of healthy adults. DESIGN: The Sleep Heart Health Study is a multicenter study examining sleep and cardiopulmonary parameters through nocturnal polysomnography in adults enrolled in geographically distinct cardiovascular cohorts. SETTING: Community setting. PARTICIPANTS: 470 subjects enrolled in the Sleep Heart Health Study (n = 6440) were selected as a 'normative' group based on screening of health conditions and daily habits that could interfere with sleep. MEASUREMENTS AND RESULTS: Home-based nocturnal polysomnography was obtained on all participants and centrally scored for sleep and respiratory parameters. Demographic and health-related data were obtained and updated at the time of the home visit. Sleep efficiency decreased by 1.6% for each 10 years of increased age. Sleep time decreased by 0.1 hours (6.0 minutes) for each 10-year age increase and was longer in women. The arousal index increased by 0.8 for each 10-year increase in age and was lower by 1.4 in women. Women had a lower mean percentage of stage 1 and stage 2 sleep. Mean percentage of slow-wave sleep was higher in women (by 6.7%). Percentage of slow-wave sleep decreased with increased age for men only (by 1.9% for each 10-year age change). CONCLUSIONS: Data suggest a clear lessening in the quantity and quality of sleep with age that appears to be more rapid in males compared to females.
Keywords: Aged; Aged, 80 and over; Cardiovascular Diseases; Circadian Rhythm; Cohort Studies; Disorders of Excessive Somnolence; Female; Health Status; Humans; Male; Middle Aged; Polysomnography; Sleep; Sleep Stages; Surveys and Questionnaires

Sleep-disordered breathing is not associated with the presence of retinal microvascular abnormalities: the Sleep Heart Health Study. - Boland, Lori L; Shahar, Eyal; Wong, Tien Y; Klein, Ronald; Punjabi, Naresh; Robbins, John A; Newman, Anne B (Sleep, 2004)
STUDY OBJECTIVE: Sleep apnea and milder forms of sleep-disordered breathing (SDB) have been associated with overt clinical cardiovascular disease, but it is unknown whether SDB is associated with arterial microvascular pathology. We examined the relation between SDB and retinal microvascular abnormalities. DESIGN: Cross-sectional study. PARTICIPANTS: Subjects were 2,927 men and women, aged 51 to 97 years, who participated in the Sleep Heart Health Study and had retinal photographs taken within approximately 3 years of overnight, unattended, at-home polysomnography. MEASUREMENTS AND RESULTS: A respiratory disturbance index (RDI), calculated as the average number of apneas and hypopneas per hour of sleep, was used as an indicator of SDB in analysis. The overall prevalence of retinopathy was slightly higher in people with higher RDI values (5.4%, 4.9%, 8.6%, and 7.6%, respectively, in increasing quartiles of RDI), but after adjustment for age, body-mass index, hypertension, diabetes, and other factors, the presence of retinopathy was not associated with SDB. With the possible exceptions of microaneurysms and generalized arteriolar narrowing, as measured by lower arteriole-to-venule ratio, specific retinal abnormalities were not associated consistently with the RDI. Relative to the first quartile of RDI, the adjusted odds ratios (95% confidence interval) for the presence of microaneurysm in the second, third, and fourth quartiles of RDI were 1.05 (0.44-2.55), 1.97 (0.89-4.37), and 1.79 (0.78-4.10), respectively. An increase of RDI from 0 to 10 was associated with a predicted decrease in arteriole-to-venule ratio of 0.01. Results were similar when analyses were conducted in normotensive and nondiabetic persons separately. CONCLUSIONS: These data do not demonstrate a notable relation between SDB and retinal abnormalities. However, since this is the first investigation of a link between retinopathy and SDB, similar studies should be conducted in other population samples to demonstrate either consistency or inconsistency of our findings across studies.
Keywords: Aged; Aged, 80 and over; Body Mass Index; Coronary Disease; Cross-Sectional Studies; Female; Humans; Hypoxia; Middle Aged; Polysomnography; Positive-Pressure Respiration; Retina; Retinal Vessels; Sleep Apnea Syndromes

Time trends in the use of beta-blockers and other pharmacotherapies in older adults with congestive heart failure. - Smith, Nicholas L; Chan, Jeannie D; Rea, Thomas D; Wiggins, Kerri L; Gottdiener, John S; Lumley, Thomas; Psaty, Bruce M (Am Heart J, 2004)
BACKGROUND: Evidence supporting pharmacotherapy of congestive heart failure (CHF) has grown substantially over the past decade and includes large, placebo-controlled trials with mortality end points. We describe beta-blocker and other medication temporal treatment trends of CHF in the Cardiovascular Health Study, a community-based cohort study of 5888 adults > or =65 years of age. METHODS: Prescription medication data were collected from hospital discharge summaries for incident CHF events and at in-study annual clinic visits for prevalent CHF cases from 1989 to 2000. Change in use of agents over time was estimated by using generalized estimating equations while adjusting for potential confounding factors of age, sex, race, and cardiovascular and pulmonary comorbidities. RESULTS: Among 1033 incident CHF events, beta-blocker use after diagnosis increased an average of 2.4 percentage points annually (95% CI, 1.5 to 3.4 points) from 1989 to 2000. The increasing trend was consistent throughout follow-up. Among participants with coronary disease and/or hypertension and among those with low ejection fractions (<45%), beta-blocker use remained flat from 1989 to 1994 and increased 4.7 points annually (2.5 to 6.9) and 10.0 points annually (6.1 to 13.8), respectively, from 1995 to 2000. Among participants without coronary disease or hypertension, there was no overall increase in use. Use of renin-angiotensin system inhibitors increased 2.3 points annually (1.0 to 3.5), digoxin use decreased 2.4 points annually (-3.6 to -1.1), and loop diuretic use remained flat between 1989 and 2000. In general, treatment trends were similar for prevalent CHF. CONCLUSIONS: Treatment of CHF has changed gradually in the 1990s and may in part reflect the influence of CHF clinical trial evidence.
Keywords: Adrenergic beta-Antagonists; Aged; Angiotensin II Type 1 Receptor Blockers; Angiotensin-Converting Enzyme Inhibitors; Cohort Studies; Drug Therapy; Drug Therapy, Combination; Female; Heart Failure; Humans; Male; Multivariate Analysis; Prevalence

Associations between retinal microvascular abnormalities and declining renal function in the elderly population: the Cardiovascular Health Study. - Edwards, Matthew S; Wilson, David B; Craven, Timothy E; Stafford, Jeanette; Fried, Linda F; Wong, Tien Y; Klein, Ronald; Burke, Gregory L; Hansen, Kimberley J (Am J Kidney Dis, 2005)
BACKGROUND: Microvascular abnormalities in the kidney are common histopathologic findings in individuals with chronic kidney disease or renal failure. These abnormalities may represent one manifestation of ongoing systemic microvascular damage. We hypothesized that retinal microvascular abnormalities, when present, would be associated with progressive renal dysfunction in elderly individuals. METHODS: The Cardiovascular Health Study (CHS) is a prospective, multicenter, cohort study initiated in 1989 designed to examine cardiovascular risk factors, morbidity, and mortality in elderly Americans. As part of an ancillary study, CHS participants underwent retinal photography in 1997 and 1998. Retinal microvascular abnormalities were assessed and graded by using standardized measures. Retinal microvascular abnormalities were defined as retinopathy (hard and soft exudates, hemorrhages, or microaneurysms) and/or retinal arteriolar abnormalities (arteriovenous nicking, focal arteriolar narrowing, or lowest quartile arteriole-venule ratio). Associations between these abnormalities and observed 4-year changes in serum creatinine levels and estimated glomerular filtration rates (eGFRs) from study years 5 to 9 (encompassing years 1994 to 2001) were examined by using regression modeling. RESULTS: A total of 1,394 CHS participants had retinal and serum creatinine data. After adjustments for age, race, sex, weight, diabetes, hypertension, angiotensin-converting enzyme inhibitor use, and proteinuria, participants with retinopathy showed a significant increase in serum creatinine level and decline in eGFR compared with those without retinopathy during the 4-year study period (+0.24 mg/dL [+21 micromol/L] versus -0.21 mg/dL [-19 micromol/L] and -0.48 mL/min/1.73 m2 [-0.01 mL/s/1.73 m2] versus +1.74 mL/min/1.73 m2 [+0.03 mL/s/1.73 m2], respectively). Participants with retinopathy also were significantly more likely to have an observed significant deterioration in renal function, defined as a 0.3-mg/dL (27-micromol/L) increase in serum creatinine level or 20% or greater decline in eGFR (odds ratio, 3.20; 95% confidence interval, 1.58 to 6.50; and odds ratio, 2.84; 95% confidence interval, 1.56 to 5.16, respectively). These associations remained in separate stratified analyses of patients with and without diabetes. The presence of retinal arteriolar abnormalities was not associated with deteriorating renal function. CONCLUSION: Retinal microvascular abnormalities defined as retinopathy were significantly associated with renal function deterioration. The observed findings were independent of effects of any associated diabetes or hypertension. These findings suggest that systemic microvascular disease may be associated with progressive renal dysfunction in the elderly population.
Keywords: African Americans; Aged; Aged, 80 and over; Aging; Antihypertensive Agents; Capillaries; Cohort Studies; Comorbidity; Creatinine; Diabetes Mellitus; Disease Progression; European Continental Ancestry Group; Female; Glomerular Filtration Rate; Humans; Hypertension; Kidney; Male; Photography; Prospective Studies; Proteinuria; Retina; Retinal Diseases; Retinal Vessels

Associations of sleep-disordered breathing and cerebral changes on MRI. - Robbins, John; Redline, Susan; Ervin, Ann; Walsleben, Joyce A; Ding, Jingzhong; Nieto, F Javier (J Clin Sleep Med, 2005)
STUDY OBJECTIVES: Population-based studies have demonstrated associations between sleep-disordered breathing (SDB), hypertension, and cardiovascular disease; few large-scale studies have examined associations of SDB with objective measures of cerebrovascular disease. This study tested the significance of associations of SDB with evidence of brain injury or ischemia determined by cerebral magnetic resonance imaging (MRI) studies. DESIGN: Cross-sectional and longitudinal analyses in a nested sample of Cardiovascular Health Study participants in the Sleep Heart Health Study. PARTICIPANTS: The 843 individuals (mean age 77, SD 4.3 years, 58% women) who had MRI studies as part of the Cardiovascular Health Study before and after polysomnography obtained as part of the Sleep Heart Health Study. MEASUREMENTS: A 12-channel polysomnogram was used to derive indexes of sleep-disordered breathing. Repeated MRI measurements provided indexes of infarct (presence and size) and white matter disease. Logistic regression analyses were used to model MRI changes of infarct-like lesions and white matter disease as a function of age, baseline white matter grade, and indexes of central and obstructive sleep-disordered breathing. RESULTS: Individuals who showed progression in white matter disease compared to those who did not were significantly more likely to show a Cheyne-Stokes respiration pattern and to have an increased number of central but not obstructive apneas. CONCLUSIONS: An association between change in white matter grade and measures of central sleep apnea was demonstrated that was consistent with a causal pathway in which central sleep apnea contributes to the progression of white matter disease; alternatively, central sleep apnea may be a marker of subclinical cerebrovascular or cardiovascular disease.
Keywords: Aged; Brain; Cerebral Infarction; Cerebrovascular Circulation; Female; Humans; Magnetic Resonance Imaging; Male; Polysomnography; Severity of Illness Index; Sleep Apnea Syndromes; Sleep Apnea, Obstructive

Cardiovascular risk factors for retinal vein occlusion and arteriolar emboli: the Atherosclerosis Risk in Communities & Cardiovascular Health studies. - Wong, Tien Yin; Larsen, Emily K Marino; Klein, Ronald; Mitchell, Paul; Couper, David J; Klein, Barbara E K; Hubbard, Larry D; Siscovick, David S; Sharrett, A Richey (Ophthalmology, 2005)
OBJECTIVE: To examine the associations of retinal vein occlusion and arteriolar emboli with cardiovascular disease. DESIGN: Population-based cross-sectional study. PARTICIPANTS: Pooled from the Atherosclerosis Risk in Communities Study (n = 12,642; mean age, 60 years) and the Cardiovascular Health Study (n = 2824; mean age, 79 years). METHODS: Retinal vein occlusion and arteriolar emboli were identified from a single nonmydriatic retinal photograph using a standardized protocol. Photographs were also graded for arteriovenous nicking and focal arteriolar narrowing. All participants had a comprehensive systemic evaluation, including standardized carotid ultrasonography. MAIN OUTCOME MEASURES: Retinal vein occlusion and arteriolar emboli. RESULTS: Prevalences of retinal vein occlusion and arteriolar emboli were 0.3% (n = 39 cases) and 0.2% (n = 34 cases), respectively. After adjusting for age, retinal vein occlusion was associated with hypertension (odds ratio [OR], 2.96; 95% confidence interval [CI], 1.43-6.14), systolic blood pressure (BP) (OR, 4.12; 95% CI, 1.40-12.16; highest quartile vs. lowest), diastolic BP (OR, 2.64; 95% CI, 1.07-6.46; highest quartile vs. lowest), carotid artery plaque (OR, 5.62; 95% CI, 2.60-12.16), body mass index (OR, 3.88; 95% CI, 1.23-12.18; highest quartile vs. lowest), plasma fibrinogen (OR, 3.29; 95% CI, 1.08-10.02; highest quartile vs. lowest), arteriovenous nicking (OR, 4.09; 95% CI, 2.00-8.36), and focal arteriolar narrowing (OR, 5.17; 95% CI, 2.59-10.29). After adjusting for age, retinal arteriolar emboli were associated with hypertension (OR, 3.14; 95% CI, 1.44-6.84), systolic BP (OR, 3.46; 95% CI, 1.13-10.65; highest quartile vs. lowest), prevalent coronary heart disease (OR, 2.33; 95% CI, 1.01-5.42), carotid artery plaque (OR, 4.62; 95% CI, 1.85-11.57), plasma lipoprotein (a) (OR, 3.69; 95% CI, 1.20-11.41; highest quartile vs. lowest), plasma fibrinogen (OR, 3.09; 95% CI, 0.98-9.76; highest quartile vs. lowest), and current cigarette smoking (OR, 3.08; 95% CI, 1.47-6.47). Approximately a quarter of participants with retinal vein occlusion and arteriolar emboli had evidence of carotid artery plaque as defined from ultrasound. CONCLUSIONS: Retinal vein occlusion and retinal arteriolar emboli are associated with carotid artery disease, hypertension, and other cardiovascular risk factors.
Keywords: Aged; Aged, 80 and over; Arterioles; Blood Pressure; Cardiovascular Diseases; Carotid Stenosis; Coronary Artery Disease; Cross-Sectional Studies; Embolism; Female; Fibrinogen; Humans; Hypertension; Lipoprotein(a); Male; Meta-Analysis as Topic; Middle Aged; Retinal Artery; Retinal Vein Occlusion; Risk Factors

Common promoter polymorphisms of inflammation and thrombosis genes and longevity in older adults: the cardiovascular health study. - Reiner, Alexander P; Diehr, Paula; Browner, Warren S; Humphries, Stephen E; Jenny, Nancy S; Cushman, Mary; Tracy, Russell P; Walston, Jeremy; Lumley, Thomas; Newman, Anne B; Kuller, Lewis H; Psaty, Bruce M (Atherosclerosis, 2005)
Inflammatory response genes may influence life span or quality at advanced ages. Using data from the population-based cardiovascular health study (CHS) cohort, we examined the associations between promoter polymorphisms of several inflammation and thrombosis genes with longevity. We ascertained genotypes for interleukin (IL)-6 -174 G/C, beta-fibrinogen -455 G/A, plasminogen activator inhibitor (PAI)-1 -675 4G/5G, and thrombin-activatable fibrinolysis inhibitor (TAFI) -438 G/A in 2224 men and women > or = 65 years old at baseline. During 10 years of follow-up, men with the TAFI -438 A/A genotype had decreased mortality due to all causes, and lived, on average, 0.9 more years of life, or 1.1 more years of healthy life, than men with the -438 G allele. The effects of TAFI -438 G/A in women were smaller and not statistically significant. PAI-1 4G/4G genotype appeared to be associated with lower non-cardiovascular mortality in men, but with greater cardiovascular mortality in women. In exploratory analyses, we observed a possible interaction among anti-inflammatory drugs, interleukin-6 -174 C/C genotype, and longevity. These findings suggest that modulators of fibrinolytic activity may have a generalized influence on aging, and merit further investigation in studies of genetic determinants of human longevity.
Keywords: Aged; Aging; Carboxypeptidase B2; Cause of Death; Cohort Studies; Female; Genotype; Health Status; Humans; Inflammation; Longevity; Male; Middle Aged; Plasminogen Activator Inhibitor 1; Polymorphism, Genetic; Promoter Regions, Genetic; Prospective Studies; Risk Factors; Thrombosis

Hospitalization for pneumonia in the Cardiovascular Health Study: incidence, mortality, and influence on longer-term survival. - O'Meara, Ellen S; White, Mark; Siscovick, David S; Lyles, Mary F; Kuller, Lewis H (J Am Geriatr Soc, 2005)
OBJECTIVES: To estimate the rate of hospitalization for pneumonia in community-dwelling older adults and to assess its risk factors and contribution to mortality. DESIGN: Prospective observational study. SETTING: The Cardiovascular Health Study (CHS) in four U.S. communities. PARTICIPANTS: Five thousand eight hundred eighty-eight men and women aged 65 and older who were followed for a median 10.7 years. MEASUREMENTS: Participants were interviewed about medical history and demographics; evaluated for lung, physical, and cognitive function; and followed for hospitalizations, cardiovascular disease, and death. RESULTS: Nearly 10% of the cohort was hospitalized for pneumonia, for a rate of 11.1 per 1,000 person-years (95% confidence interval (CI)=10.2-12.0). Risk factors included older age, male sex, current and past smoking, poor physical and lung function, and history of cardiovascular disease and chronic obstructive pulmonary disease. Ten percent of participants died during their incident pneumonia hospitalization, and death rates were high in those who survived to discharge. Compared with participants who had not been hospitalized for pneumonia, the relative risk of total mortality was 4.9 (95% CI=4.1-6.0) during the first year after hospitalization and 2.6 (95% CI=2.2-3.1) thereafter, adjusted for age, sex, and race. The respective relative risks were 3.9 (95% CI=3.1-4.8) and 2.0 (95% CI=1.6-2.4) after further adjustment for baseline history of cardiovascular disease; diabetes mellitus; smoking; and measures of lung, physical, and cognitive function. CONCLUSION: In older people, hospitalization for pneumonia is common and is associated with an elevated risk of death, as shown in this population-based, prospective cohort.
Keywords: Aged; Aged, 80 and over; Cognition; Comorbidity; Diabetes Complications; Female; Hospitalization; Humans; Male; Mortality; Pneumonia; Prospective Studies; Respiratory Physiological Phenomena; Risk Factors; Smoking

Prostate carcinoma incidence in relation to prediagnostic circulating levels of insulin-like growth factor I, insulin-like growth factor binding protein 3, and insulin. - Chen, Chu; Lewis, S Kay; Voigt, Lynda; Fitzpatrick, Annette; Plymate, Stephen R; Weiss, Noel S (Cancer, 2005)
BACKGROUND: There have been several epidemiologic studies investigating the association between circulating levels of insulin-like growth factor I (IGF-I), insulin-like growth factor binding protein 3 (IGFBP-3), and insulin in relation to the risk of prostate carcinoma, with conflicting results. To examine this issue further, the authors conducted a nested case-control study within the Cardiovascular Health Study cohort. METHODS: In men who were diagnosed with prostate carcinoma (cases) between 1990 and 1999 (n=174), the levels of IGF-I, IGFBP-3, and insulin were measured on blood samples that were obtained 1-9 years prior to diagnosis (mean, 3.4 years). Similar measurements were made on 174 male participants without prostate carcinoma (controls) who were matched to cases based on the year blood was drawn, survival until the date of diagnosis, race, and age. RESULTS: Relative to the men with IGF-I levels in the first (lowest) quartile of the distribution, the risk of prostate carcinoma for men in the second, third, and fourth (upper) quartiles were 0.77 (95% confidence interval [95% CI], 0.43-1.38), 0.73 (95% CI, 0.41-1.30), and 0.67 (95% CI, 0.37-1.25), respectively. The results were influenced little by adjustment for levels of IGFBP-3 or, instead, by evaluating the molar IGF-I/IGFBP-3 ratio. An analysis that was restricted to men who had plasma prostate-specific antigen levels <4 ng/mL at the time of the blood draw yielded similar results. The corresponding relative risks for IGFBP-3 were 0.91 (95% CI, 0.49-1.68), 0.47 (95% CI, 0.25-0.94), and 0.65 (95% CI, 0.35-1.20), respectively. The distribution of serum insulin levels in cases and controls were nearly identical. CONCLUSIONS: The IGF-I level was not associated positively with the risk of prostate carcinoma; however, an increase in the IGFBP-3 level was associated with a modest decrease in risk.
Keywords: Aged; Aged, 80 and over; Carcinoma; Case-Control Studies; Humans; Hypoglycemic Agents; Incidence; Insulin; Insulin-Like Growth Factor Binding Protein 3; Insulin-Like Growth Factor I; Male; Prostatic Neoplasms; Risk Factors

The association of microalbuminuria with clinical cardiovascular disease and subclinical atherosclerosis in the elderly: the Cardiovascular Health Study. - Cao, Jie J; Barzilay, Joshua I; Peterson, Do; Manolio, Teri A; Psaty, Bruce M; Kuller, Lewis; Wexler, Jason; Bleyer, Anthony J; Cushman, Mary (Atherosclerosis, 2006)
PURPOSE: Microalbuminuria (MA) is a risk factor for cardiovascular disease (CVD). It is not known whether this association is due to the effect of MA on the development of subclinical atherosclerosis or whether MA destabilizes subclinical atherosclerosis, leading to clinical events. METHODS: In a cross-sectional analysis we evaluated 3312 Cardiovascular Health Study participants, age >or=65 years, who had MA testing. Participants were divided into three groups: those without diabetes or hypertension (33%), those with hypertension (52%) and those with diabetes, with or without hypertension (15%). Clinical CVD was defined as presence of coronary heart disease (angina, MI, CABG, PTCA), cerebrovascular disease (stroke, TIA) and peripheral arterial disease (requiring intervention). Among those without clinical disease, subclinical atherosclerosis was defined as increased carotid artery intima-media thickness, decreased ankle arm index or increased left ventricular mass. RESULTS: In each of the three groups of participants, the adjusted odds of prevalent clinical CVD in the presence of MA was 1.70-1.80-fold increased, independent of other risk factors. MA was not associated with risk of subclinical atherosclerosis in those without hypertension or diabetes (OR 1.14 [95% CI 0.59, 2.23]), whereas it was associated with subclinical atherosclerosis in those with hypertension (OR 1.58 [95% CI 1.08, 2.30]) or diabetes (OR 2.51 [95% CI 1.27, 4.94]). CONCLUSION: In the absence of hypertension or diabetes, MA was associated with clinical CVD but not with subclinical atherosclerosis. Thus, a hypothesis may be made that the mechanism of association of MA with clinical vascular disease involves destabilization of the vasculature, leading to clinical disease.
Keywords: Aged; Aged, 80 and over; Albuminuria; Atherosclerosis; Cardiovascular Diseases; Coronary Disease; Diabetes Mellitus; Female; Humans; Hypertension; Male; Peripheral Vascular Diseases; Prevalence; Risk Factors; Stroke; United States

Association of polymorphisms in the CRP gene with circulating C-reactive protein levels and cardiovascular events. - Lange, Leslie A; Carlson, Christopher S; Hindorff, Lucia A; Lange, Ethan M; Walston, Jeremy; Durda, J Peter; Cushman, Mary; Bis, Joshua C; Zeng, Donglin; Lin, Danyu; Kuller, Lewis H; Nickerson, Deborah A; et al. (JAMA, 2006)
CONTEXT: C-reactive protein (CRP) is an inflammation protein that may play a role in the pathogenesis of cardiovascular disease (CVD). OBJECTIVE: To assess whether polymorphisms in the CRP gene are associated with plasma CRP, carotid intima-media thickness (CIMT), and CVD events. DESIGN, SETTING, AND PARTICIPANTS: In the prospective, population-based Cardiovascular Health Study, 4 tag single-nucleotide polymorphisms (SNPs) (1919A/T, 2667G/C, 3872G/A, 5237A/G) were genotyped in 3941 white (European American) participants and 5 tag SNPs (addition of 790A/T) were genotyped in 700 black (African American) participants, aged 65 years or older, all of whom were without myocardial infarction (MI) or stroke before study entry. Median follow-up was 13 years (1989-2003). MAIN OUTCOME MEASURES: Baseline CIMT; occurrence of MI, stroke, and CVD mortality during follow-up. RESULTS: In white participants, 461 incident MIs, 491 incident strokes, and 490 CVD-related deaths occurred; in black participants, 67 incident MIs, 78 incident strokes, and 75 CVD-related deaths occurred. The 1919T and 790T alleles were associated with higher CRP levels in white and black participants, respectively. The 3872A allele was associated with lower CRP levels in both populations, and the 2667C allele was associated with lower CRP levels in white participants only. There was no association between CIMT and any CRP gene polymorphism in either population. In white participants, the 1919T allele was associated with increased risk of stroke for TT vs AA (hazard ratio [HR], 1.40; 95% confidence interval [CI], 1.06-1.87) and for CVD mortality (HR, 1.40; 95% CI, 1.10-1.90). In black participants, homozygosity for the 790T allele was associated with a 4-fold increased risk of MI compared with homozygosity for the 790A allele (95% CI, 1.58-10.53). The minor alleles of the 2 SNPs associated with lower plasma CRP concentration in white participants (2667C and 3872A) were associated with decreased risk of CVD mortality. CONCLUSIONS: Genetic variation in the CRP gene is associated with plasma CRP levels and CVD risk in older adults.
Keywords: African Continental Ancestry Group; Aged; C-Reactive Protein; Cardiovascular Diseases; Carotid Arteries; European Continental Ancestry Group; Female; Genotype; Humans; Male; Myocardial Infarction; Polymorphism, Single Nucleotide; Proportional Hazards Models; Risk; Stroke; Tunica Intima

CFH, ELOVL4, PLEKHA1 and LOC387715 genes and susceptibility to age-related maculopathy: AREDS and CHS cohorts and meta-analyses. - Conley, Yvette P; Jakobsdottir, Johanna; Mah, Tammy; Weeks, Daniel E; Klein, Ronald; Kuller, Lewis; Ferrell, Robert E; Gorin, Michael B (Hum Mol Genet, 2006)
Age-related maculopathy (ARM) is an important cause of visual impairment in the elderly population. It is of crucial importance to identify genetic factors and their interactions with environmental exposures for this disorder. This study was aimed at investigating the CFH, ELOVL4, PLEKHA1 and LOC387715 genes in independent cohorts collected using different ascertainment schemes. The study used a case-control design with subjects originally recruited through the Cardiovascular Health Study (CHS) and the Age-Related Eye Disease Study (AREDS). CFH was significantly associated with ARM in both cohorts (P</=0.00001). A meta-analysis confirmed that the risk allele in the heterozygous or homozygous state (OR, 2.4 and 6.2; 95% CI, 2.2-2.7 and 5.4-7.2, respectively) confers susceptibility. LOC387715 was also significantly associated with ARM in both cohorts (P</=0.00001) and a meta-analysis confirmed that the risk allele in the heterozygous and homozygous state (OR, 2.5 and 7.3; 95% CI, 2.2-2.9 and 5.7-9.4, respectively) confers susceptibility. Both CFH and LOC387715 showed an allele-dose effect on the ARM risk, individuals homozygous at either locus were at more than two-fold risk compared to those heterozygous. PLEKHA1, which is closely linked to LOC387715, was significantly associated with ARM status in the AREDS cohort, but not the CHS cohort and ELOVL4 was not significantly associated with ARM in either cohort. Joint action of CFH and LOC387715 was best described by independent multiplicative effect without significant interaction in both cohorts. Interaction of both genes with cigarette smoking was insignificant in both cohorts. This study provides additional support for the CFH and LOC387715 genes in ARM susceptibility via the evaluation of cohorts that had different ascertainment schemes regarding ARM status and through the meta-analyses.
Keywords: Aged; Aged, 80 and over; Case-Control Studies; Cohort Studies; Complement Factor H; Eye Proteins; Female; Genetic Predisposition to Disease; Humans; Intracellular Signaling Peptides and Proteins; Macular Degeneration; Male; Membrane Proteins; Proteins

Clinical course of mesenteric artery stenosis in elderly americans. - Wilson, David B; Mostafavi, Kian; Craven, Timothy E; Ayerdi, Juan; Edwards, Matthew S; Hansen, Kimberley J (Arch Intern Med, 2006)
BACKGROUND: To examine prospectively the relationship between stenosis or occlusion of the celiac and superior mesenteric arteries and symptoms of chronic intestinal ischemia in free-living elderly patients in the United States. METHODS: As part of an ancillary study to the Cardiovascular Health Study, participants in the Forsyth County (North Carolina) cohort underwent visceral duplex ultrasonography of the celiac and superior mesenteric arteries. Critical mesenteric artery stenosis (MAS) or occlusion was defined by Doppler flow ultrasound-derived criteria. Clinical outcomes were assessed at annual follow-up examinations and review of death certificates. Multivariate associations between the presence of MAS and all-cause mortality and adverse cardiovascular events were analyzed. Participants with MAS were contacted to determine the presence of symptoms consistent with chronic intestinal ischemia. RESULTS: Of 553 participants who underwent visceral duplex ultrasonography, 97 (17.5%) had disease of the celiac or superior mesenteric artery. At a mean follow-up of 6(1/2) years, 20 participants with MAS (20.6%) and 93 without MAS (20.4%) had died (relative risk, 1.01; 95% confidence interval, 0.66-1.55). No deaths were attributed to intestinal infarction. No association existed between the presence of MAS and prevalent cardiovascular disease, all-cause mortality, or adverse cardiovascular events. A questionnaire was completed by 71% of the surviving participants with MAS. No participant reported symptoms or weight loss consistent with chronic intestinal ischemia. CONCLUSIONS: Mesenteric artery stenosis was a common finding in free-living elderly patients. At long-term follow-up, the presence of asymptomatic MAS was not associated with death or adverse cardiovascular events. Participants with asymptomatic MAS by duplex ultrasonographic criteria did not experience intestinal infarction or develop chronic intestinal ischemia.
Keywords: Aged; Aged, 80 and over; Cohort Studies; Comorbidity; Female; Humans; Male; Mesenteric Arteries; Mesenteric Vascular Occlusion; Proportional Hazards Models; Prospective Studies; Radiography; Risk Factors; Surveys and Questionnaires; Ultrasonography

Costs for heart failure with normal vs reduced ejection fraction. - Liao, Lawrence; Jollis, James G; Anstrom, Kevin J; Whellan, David J; Kitzman, Dalane W; Aurigemma, Gerard P; Mark, Daniel B; Schulman, Kevin A; Gottdiener, John S (Arch Intern Med, 2006)
BACKGROUND: Among the elderly population, heart failure (HF) with normal ejection fraction (EF) is more common than classic HF with low EF. However, there are few data regarding the costs of HF with normal EF. In a prospective, population-based cohort of elderly participants, we compared the costs and resource use of patients with HF and normal and reduced EF. METHODS: A total of 4549 participants (84.5% white; 40.6% male) in the National Heart, Lung, and Blood Institute Cardiovascular Health Study were linked to Medicare claims from 1992 through 1998. By protocol echo examinations or clinical EF assessments, 881 participants with HF were characterized as having abnormal or normal EF. We applied semiparametric estimators to calculate mean costs per subject for a 5-year period. RESULTS: There were 495 HF participants with normal EF (186 prevalent at study entry and 309 incident during the study period) and 386 participants with abnormal EF (166 prevalent and 220 incident). Participants with abnormal EF had more cardiology encounters and cardiac procedures. However, compared with abnormal EF participants, the 5-year costs for normal EF participants were similar in both the prevalent ($33,023 with abnormal EF and $32,580 with normal EF; P=.93) and incident ($49,128 with abnormal EF and $45,604 with normal EF; P=.55) groups. In models accounting for comorbid conditions, the costs with normal and abnormal EF remained similar. CONCLUSIONS: Over a 5-year period, patients with HF and normal EF consume as many health care resources as those with reduced EF. These data highlight the substantial financial burden of HF with normal EF among the elderly population.
Keywords: Aged; Aged, 80 and over; Comorbidity; Echocardiography; Health Care Costs; Heart Failure; Humans; Incidence; Medicare; Prevalence; Prospective Studies; Regression Analysis; Statistics, Nonparametric; Stroke Volume; Systole; United States; Ventricular Function, Left

Depressive symptoms, vascular disease, and mild cognitive impairment: findings from the Cardiovascular Health Study. - Barnes, Deborah E; Alexopoulos, George S; Lopez, Oscar L; Williamson, Jeff D; Yaffe, Kristine (Arch Gen Psychiatry, 2006)
CONTEXT: Depressive symptoms are common in patients with dementia and may be associated with increased risk of developing dementia. It has been hypothesized that depressive symptoms and dementia may be attributable to underlying vascular disease in some older persons. OBJECTIVES: To test the hypotheses (1) that depressive symptoms are associated with increased risk of developing mild cognitive impairment (MCI), a preclinical state that often precedes dementia, and (2) that the association between depressive symptoms and MCI is attributable to underlying vascular disease. DESIGN: Prospective, population-based, longitudinal study. SETTING: Random sample of adults 65 years or older recruited from 4 US communities. PARTICIPANTS: Subjects were 2220 participants in the Cardiovascular Health Study Cognition Study with high cognitive function at baseline. Depressive symptoms were measured at baseline using the 10-item Center for Epidemiological Studies Depression Scale and were classified as none (0-2 points), low (3-7 points), and moderate or high (>/=8 points). Vascular disease measures at baseline included confirmed history of stroke, transient ischemic attack, diabetes mellitus, or hypertension; carotid artery stenosis; ankle-arm blood pressure index; and small or large infarcts or white matter disease on cerebral magnetic resonance imaging. Mild cognitive impairment was diagnosed after 6 years of follow-up based on the consensus of a team of dementia experts using standard clinical criteria. MAIN OUTCOME MEASURE: Diagnosis of MCI. RESULTS: Depressive symptoms at baseline were associated with increased risk of MCI (10.0%, 13.3%, and 19.7% for those with no, low, and moderate or high depressive symptoms, respectively). This association was diminished only slightly by adjustment for vascular disease measures and demographics. Vascular disease measures also were associated with increased risk of MCI, and these associations were not diminished by adjustment for depressive symptoms or demographics. CONCLUSION: Depressive symptoms were associated with increased risk of MCI, and this association was independent of underlying vascular disease.
Keywords: Aged; Cerebrovascular Disorders; Cognition Disorders; Comorbidity; Dementia; Dementia, Vascular; Depressive Disorder; Female; Follow-Up Studies; Geriatric Assessment; Humans; Longitudinal Studies; Male; Prospective Studies; Psychiatric Status Rating Scales; Risk Factors; Sampling Studies; Vascular Diseases

Metabolic syndrome and cardiovascular disease in older people: The cardiovascular health study. - McNeill, Ann Marie; Katz, Ronit; Girman, Cynthia J; Rosamond, Wayne D; Wagenknecht, Lynne E; Barzilay, Joshua I; Tracy, Russell P; Savage, Peter J; Jackson, Sharon A (J Am Geriatr Soc, 2006)
OBJECTIVES: To assess the prospective association between metabolic syndrome (MetS) and cardiovascular disease (CVD) in older people and to evaluate the effect of lowering the threshold for impaired fasting glucose (IFG) on the prevalence of IFG and MetS and the risk of CVD. DESIGN: Prospective cohort study. SETTING: Four field centers in U.S. communities. PARTICIPANTS: Three thousand five hundred eighty-five subjects in the Cardiovascular Health Study free of diabetes mellitus and CVD at baseline (mean age 72, 62% female, 14% black). MEASUREMENTS: Baseline measures of MetS components and adjudicated incident CVD events. MetS (2001) was defined first using the original criteria from the Third Adult Treatment Panel Report of the National Cholesterol Education Program (> or =3 of the following: large waist circumference (women >88 cm, men >102 cm), elevated triglycerides (> or =1.70 mmol/L), low high-density lipoprotein cholesterol (men <1.04 mmol/L, women <1.30 mmol/L), elevated fasting glucose (6.1-6.9 mmol/L), and high blood pressure (> or =130/85 mmHg or self-reported use of medications for hypertension). Subjects were also classified according to the revised definition of the MetS (2005) that applies the lower threshold for fasting glucose (5.6-6.9 mmol/L). RESULTS: During follow-up (median 11 years), 818 coronary heart disease (CHD), 401 stroke, and 554 congestive heart failure (CHF) events occurred. Age- and race-adjusted hazard ratios (HRs) for CHD, stroke, and CHF were 1.30 (95% confidence interval (CI) = 1.07-1.57), 0.94 (95% CI = 0.73-1.21), and 1.40 (95% CI = 1.12-1.76) for women and 1.35 (95% CI = 1.10-1.66), 1.51 (95% CI = 1.08-2.12), and 1.47 (95% CI = 1.14-1.90) for men, respectively. Overall, women and men with MetS (2005) were 20% to 30% more likely to experience any CVD event than subjects without MetS (2005). Using the lower cut-point for IFG resulted in a near tripling in IFG prevalence (16% to 46%) and an additional 9% classified with MetS (2005) but HRs similar to those estimated from the original MetS (2001) criteria. High blood pressure was the component most strongly associated with incident CHD. CONCLUSION: Results from this study of an elderly, population-based cohort provide support for earlier investigations in primarily middle-aged populations that link the presence of MetS with the development of CVD and further underscore the importance of recognizing and treating its individual components, particularly high blood pressure.
Keywords: African Americans; Age Factors; Aged; Aged, 80 and over; Blood Glucose; Cardiovascular Diseases; Cohort Studies; European Continental Ancestry Group; Fasting; Female; Humans; Incidence; Male; Metabolic Syndrome; Risk Factors; Sex Factors

Obstructive sleep apnea and plasma natriuretic peptide levels in a community-based sample. - Patwardhan, Anjali A; Larson, Martin G; Levy, Daniel; Benjamin, Emelia J; Leip, Eric P; Keyes, Michelle J; Wang, Thomas J; Gottlieb, Daniel J; Vasan, Ramachandran S (Sleep, 2006)
STUDY OBJECTIVES: We hypothesized that alterations in cardiac hemodynamics associated with obstructive sleep apnea-hypopnea (OSAH) would be reflected in higher natriuretic peptide levels. We examined the association of OSAH with natriuretic peptides in a community-based sample. DESIGN: Cross-sectional, retrospective, observational study. SETTING: Framingham Heart Study Offspring Cohort and Sleep Heart Health Study. PARTICIPANTS: Community-based sample of 623 individuals. MEASUREMENTS: Full-montage home polysomnography was used to determine apnea-hypopnea index (AHI) and percentage of time with an oxyhemoglobin saturation < 90% (PctLt90). Sensitive immunoradiometric assays were used to measure plasma B-type (BNP) and N-terminal pro-atrial natriuretic peptide (NT-ANP). Multivariable regression was used to examine the relations between natriuretic peptides and indicators of OSAH, adjusting for age, sex, body mass index, and clinical covariates. RESULTS: No statistically significant relations between OSAH indices and BNP were observed in the multivariable model. Compared with an AHI < 5, relative levels of 1.20, 0.88, and 0.91 were observed forAHI categories 5-15, 15-30, >30 events per hour, respectively. For NT-ANP, no significant relations were seen with AHI in the multivariable model (relative levels of 0.98, 0.91, and 0.90). An inverse association was observed between NT-ANP and PctLt90 in age- and sex-adjusted models (relative levels of 0.93, 0.87, and 0.80), although this association became statistically nonsignificant after adjusting for body mass index. CONCLUSION: Lack of association of natriuretic peptides with OSAH indices suggests that undiagnosed OSAH may not be associated with major alterations in left ventricular function, as reflected in morning natriuretic peptide levels.
Keywords: Atrial Fibrillation; Body Mass Index; Cohort Studies; Female; Humans; Hypertension; Male; Middle Aged; Myocardial Infarction; Natriuretic Peptides; Obesity; Polysomnography; Prevalence; Residence Characteristics; Severity of Illness Index; Sleep Apnea, Obstructive

Obstructive sleep apnea-hypopnea and neurocognitive functioning in the Sleep Heart Health Study. - Quan, Stuart F; Wright, Ron; Baldwin, Carol M; Kaemingk, Kristine L; Goodwin, James L; Kuo, Tracy F; Kaszniak, Alfred; Boland, Lori L; Caccappolo, Elise; Bootzin, Richard R (Sleep Med, 2006)
BACKGROUND AND PURPOSE: Obstructive sleep apnea-hypopnea (OSAH) is associated with sleep fragmentation and nocturnal hypoxemia. In clinical samples, patients with OSAH frequently are found to have deficits in neuropsychological function. However, the nature and severity of these abnormalities in non-clinical populations is less well defined. PATIENTS AND METHODS: One hundred and forty-one participants from the Tucson, AZ and New York, NY field centers of the Sleep Heart Health Study completed a battery of neuropsychological tests for 9-40 months (mean=24 months, SD=7 months) after an unattended home polysomnogram. Sixty-seven participants had OSAH (AHI>10) and 74 did not have OSAH (control (CTL), apnea-hypopnea index (AHI)<5). In addition to the individual tests, composite variables representing attention, executive function, MotorSpeed and processing speed were constructed from the neuropsychological test battery. RESULTS: There were no significant differences in any individual neuropsychological test or composite variable between the OSAH and CTL groups. However, when time spent with O(2) saturations less than 85% was dichotomized into those participants in the top quartile of the distribution and those in the lower three quartiles, motor speed was significantly impaired in those who were more hypoxemic. In addition, poorer motor speed (model adjusted R(2)=0.242, P<0.001) and processing speed performance (model adjusted R(2)=0.122, P<0.001) were associated with more severe oxygen desaturation even after controlling for degree of daytime sleepiness, age, gender and educational level. CONCLUSIONS: Mild to moderate OSAH has little impact on the selected measures of attention, executive function, motor speed and processing speed. However, hypoxemia adversely affects both motor and processing speed. These results suggest that in middle-aged to elderly adults the neuropsychological effects of clinically unrecognized mild to moderate OSAH are neither global nor large.
Keywords: Brain; Cognition Disorders; Continuous Positive Airway Pressure; Demography; Disorders of Excessive Somnolence; Electromyography; Electrooculography; Female; Health Status; Humans; Hypoxia; Male; Middle Aged; Neuropsychological Tests; Oxygen; Polysomnography; Severity of Illness Index; Sleep Apnea, Obstructive; Surveys and Questionnaires

Quantitative retinal venular caliber and risk of cardiovascular disease in older persons: the cardiovascular health study. - Wong, Tien Yin; Kamineni, Aruna; Klein, Ronald; Sharrett, A Richey; Klein, Barbara E; Siscovick, David S; Cushman, Mary; Duncan, Bruce B (Arch Intern Med, 2006)
BACKGROUND: Small vessel disease may contribute to the risk of cardiovascular disease in older persons. We describe the relation of retinal vascular caliber to incident coronary heart disease (CHD) and stroke in elderly persons. METHODS: Prospective population-based cohort study composed of 1992 men and women aged 69 to 97 years living in 4 US communities. Retinal arteriolar and venular calibers were measured from retinal photographs using a computer-assisted method. Incident CHD and stroke events were ascertained using standardized methods. RESULTS: After 5 years of follow-up, there were 115 incident CHD events and 113 incident stroke events. Participants with larger retinal venular caliber had a higher incidence of CHD (11.7%; 95% confidence interval [CI], 8.7%-15.8%, vs 8.1%; 95% CI, 5.7%-11.6%), comparing largest with smallest venular caliber quartiles, and stroke (8.4%; 95% CI, 6.0-11.7, vs 5.8%; 95% CI, 3.9-8.4). At multivariable analysis, controlling for age, sex, race, arteriolar caliber, systolic and diastolic blood pressure, diabetes, glucose concentration, cigarette smoking, pack-years of smoking, and high-density-lipoprotein and low-density lipoprotein cholesterol levels, larger retinal venular caliber was associated with incident CHD (rate ratio, 3.0; 95% CI, 1.6-5.7, comparing largest with smallest venular caliber quartiles; P(trend) = .001) and incident stroke (rate ratio, 2.2; 95% CI, 1.1-4.3; P(trend) = .02). Additional adjustment for C-reactive protein and common and internal carotid artery intimal-media thickness had minimal effect on these associations. At multivariable analysis, smaller retinal arteriolar caliber was associated with incident CHD (rate ratio, 2.0; 95% CI, 1.1-3.7, comparing largest with smallest arteriolar caliber quartiles; P = .03) but not stroke (rate ratio,1.1; 95% CI, 0.5-2.2; P = .73). CONCLUSION: Larger retinal venular caliber is independently associated with risk of cardiovascular disease in elderly persons.
Keywords: Aged; Aged, 80 and over; Algorithms; Cardiovascular Diseases; Cohort Studies; Female; Humans; Image Processing, Computer-Assisted; Incidence; Male; Photography; Prospective Studies; Retinal Diseases; Retinal Vein; Retinal Vessels; Risk Factors; Stroke; United States

Regression dilution methods for meta-analysis: assessing long-term variability in plasma fibrinogen among 27,247 adults in 15 prospective studies. - Wood, Angela M; White, Ian; Thompson, Simon G; Lewington, Sarah; Danesh, John (Int J Epidemiol, 2006)
BACKGROUND: Within-person variability in measured values of a risk factor can bias its association with disease. The extent of this regression dilution bias for plasma fibrinogen was investigated using repeat measurement data collected at varying time intervals on 27 247 adults in 15 prospective studies. METHODS: Regression dilution ratios (RDRs) were estimated from a linear regression of repeat measurements on baseline values in each study and for each time interval, and pooled allowing for within- and between-study heterogeneity. RDRs were estimated both without and with adjustment for confounders, and factors were investigated that might influence the RDRs. RESULTS: The unadjusted overall RDR was 0.51 (95% CI: 0.47, 0.55), which decreased to 0.46 (95% CI: 0.42, 0.49) after adjustment for age, sex and measured values of other established vascular risk factors. The RDR did not vary materially by assay method, age, sex or smoking status, but decreased at higher levels of baseline fibrinogen. CONCLUSION: It is appropriate to use an RDR of 0.5 to correct approximately for regression dilution bias in plasma fibrinogen values; however, this correction factor may produce somewhat conservative hazard ratios in adjusted analyses, at higher fibrinogen concentrations and in follow-up beyond a decade. More generally, the methods described in this report have widespread applicability to quantifying regression dilution bias in repeatability data from multiple prospective studies.
Keywords: Adult; Age Factors; Bias; Cardiovascular Diseases; Female; Fibrinogen; Humans; Male; Meta-Analysis as Topic; Prospective Studies; Regression Analysis; Risk Factors; Sex Factors; Smoking; Time Factors

Apolipoprotein e gene and age-related maculopathy in older individuals: the cardiovascular health study. - Tikellis, Gabriella; Sun, Cong; Gorin, Michael B; Klein, Ronald; Klein, Barbara E K; Larsen, Emily K Marino; Siscovick, David S; Hubbard, Larry D; Wong, Tien Y (Arch Ophthalmol, 2007)
OBJECTIVE: To examine the association between the apolipoprotein E (APOE) gene and age-related maculopathy (ARM) in an older population. METHODS: Two thousand one hundred seventy persons 65 years and older sampled from 4 US communities had ARM signs assessed from retinal photographs using a modified Wisconsin Age-Related Maculopathy Grading System. DNA extracted from blood samples was analyzed for common APOE alleles. RESULTS: After controlling for age, sex, cigarette smoking, and other factors, white participants carrying the epsilon2 allele had an increased risk of late ARM (odds ratio, 2.53 [95% confidence interval, 1.08-5.90]) while carriers of the epsilon4 allele had a lower risk of late ARM (odds ratio, 0.69 [95% confidence interval, 0.19-2.50]). There were too few late ARM cases in African American individuals for analysis. CONCLUSION: APOE polymorphism is associated with late ARM in older white persons 65 years and older. Consistent with previous studies, the APOE epsilon2 allele is associated with a significant increased risk of late ARM development, whereas the epsilon4 allele may confer some protection.
Keywords: African Americans; Aged; Aged, 80 and over; Alleles; Apolipoprotein E2; Apolipoprotein E3; Apolipoprotein E4; Cardiovascular Diseases; European Continental Ancestry Group; Female; Genotype; Humans; Macular Degeneration; Male; Odds Ratio; Polymorphism, Genetic; Risk Factors

Apolipoprotein E gene and retinal microvascular signs in older people: the Cardiovascular Health Study. - Sun, Cong; Tikellis, Gabriella; Liew, Gerald; Klein, Ronald; Larsen, Emily K Marino; Wong, Tien Y (Mol Vis, 2007)
PURPOSE: To examine the association between apolipoprotein E (APOE) gene polymorphism and retinal microvascular signs in an older population. METHODS: Retinal photographs were taken of 2,152 participants (1,831 whites, and 321 African-Americans), aged 69-96 years, who were participating in a population-based study of four United States communities. We used standardized protocols to assess photographs for the presence of retinal microvascular signs (retinopathy, arterio-venous nicking, and focal arteriolar narrowing) and a computer-assisted method to measure retinal vessel diameters. We analyzed DNA extracted from blood samples of participants for common allelic variants of the APOE gene. RESULTS: After adjusting for age, gender, systolic blood pressure, smoking, total serum cholesterol, and other risk factors, we found white participants carrying the epsilon2 and epsilon4 alleles were more likely to have arterio-venous nicking than the epsilon3/epsilon3 homozygotes, with odds ratio (OR) of 1.70 and confidence interval (CI) 95% (1.03-2.83) for the epsilon2 carriers and OR 1.74 (95% CI 1.06-2.84) for the epsilon4 carriers. Among white participants without hypertension, the associations remained significant for the epsilon4 carriers (OR 2.32, 95% CI 1.18-4.57). Whites, normotensive carriers of the epsilon2 allele had significantly narrower retinal arteriolar diameters (adjusted mean arteriolar diameter of 163.5 mum, 95% CI 160.1-167.0, p=0.03) compared to the epsilon3/epsilon3 homozygotes (167.8 mum, 95% CI 166.0-169.6). APOE gene polymorphism was not associated with retinopathy, focal narrowing, or retinal venular diameters in white participants. There were insufficient numbers of African-Americans for separate multivariate analysis. CONCLUSIONS: This study provides little evidence that the APOE gene polymorphism plays a significant role in the pathogenesis of retinal microvascular changes in the general population. In the older white population, APOE epsilon2 and epsilon4 allele carriers were more likely to have arterio-venous nicking. Other retinal signs, however, were not related to APOE gene polymorphism.
Keywords: Aged; Aged, 80 and over; Apolipoprotein E2; Apolipoprotein E4; Apolipoproteins E; European Continental Ancestry Group; Female; Gene Frequency; Genotype; Heterozygote; Homozygote; Humans; Male; Microcirculation; Polymorphism, Genetic; Retinal Diseases; Retinal Vessels

Are microvascular abnormalities in the retina associated with depression symptoms? The Cardiovascular Health Study. - Sun, Cong; Tikellis, Gabriella; Klein, Ronald; Steffens, David C; Larsen, Emily K Marino; Siscovick, David S; Klein, Barbara E K; Wong, Tien Y (Am J Geriatr Psychiatry, 2007)
OBJECTIVE: Depression has been linked with vascular risk factors and stroke. The authors examined the relationship between retinal microvascular abnormalities and depression symptoms in an elderly population. METHODS: The Cardiovascular Health Study is a population-based study conducted in four U.S. communities initiated in 1989-1990. A total of 2,420 persons aged 65 years and older were included in the current analyses. During the 1997-1998 examination, retinal photographs were performed and assessed for retinal microvascular abnormalities (retinopathy, focal arteriolar narrowing, arteriovenous nicking, generalized retinal arteriolar narrowing, and generalized retinal venular dilation) according to standardized methods. Depression symptoms were assessed by a modified version of the Centers for Epidemiologic Studies Depression (CES-D) scale annually from 1989 through 1997-1998 and was defined as a CES-D score of >9. RESULTS: Participants with retinal microvascular abnormalities were not more likely to have depression symptoms, with adjusted odds ratio (OR) (95% confidence intervals) of 1.08 (0.71-1.65) for retinopathy, OR 1.09 (0.71-1.68) for focal arteriolar narrowing, OR 0.85 (0.52-1.40) for arteriovenous nicking, OR 0.97 (0.70-1.34) for generalized arteriolar narrowing, and OR 0.79 (0.56-1.12) for generalized venular dilation. Retinal microvascular abnormalities were not related to depression symptoms in multinomial logistic regression comparing the three top quartiles of the depression CES-D scores with the lowest quartile. CONCLUSIONS: Our study did not find an association between retinal microvascular abnormalities and depression symptoms in older people.
Keywords: Aged; Aged, 80 and over; Body Mass Index; Cardiovascular Diseases; Cohort Studies; Comorbidity; Cross-Sectional Studies; Depression; Female; Fluorescein Angiography; Humans; Male; Microcirculation; Personality Inventory; Retinal Artery Occlusion; Retinal Diseases; Retinal Vein Occlusion; Risk Factors; Statistics as Topic; United States

Associations between findings on cranial magnetic resonance imaging and retinal photography in the elderly: the Cardiovascular Health Study. - Longstreth, Wt; Larsen, Emily K Marino; Klein, Ronald; Wong, Tien Yin; Sharrett, A Richey; Lefkowitz, David; Manolio, Teri A (Am J Epidemiol, 2007)
Associations between findings on cranial magnetic resonance imaging (MRI) and retinal photographs have been described mostly in middle-aged people. In the Cardiovascular Health Study, 1,717 elderly participants underwent MRI and retinal photography between 1991 and 1999. Associations were sought between MRI findings and four findings of retinal microvascular disease: retinopathy, focal arteriolar narrowing, arteriovenous nicking, and the arteriovenous ratio--the last based upon semiautomated measurements of arterioles and venules. After controlling for age and gender, the authors found associations between MRI findings and the smaller arteriovenous ratio (per standard deviation decrease): prevalent infarcts (odds ratio = 1.18, 95% confidence interval: 1.05, 1.34; p = 0.007), white matter grade (regression coefficient, 0.093; p = 0.011), incident infarct (odds ratio = 1.26, 95% confidence interval: 1.09, 1.46; p = 0.002), and worsening white matter grade (odds ratio = 1.12, 95% confidence interval: 0.98, 1.29; p = 0.09). Arteriovenous nicking was also associated with prevalent (odds ratio = 1.84, 95% confidence interval: 1.23, 2.76; p = 0.003) and incident (odds ratio = 1.84, 95% confidence interval: 1.15, 2.94; p = 0.011) infarcts. Adjustment for hypertension and diabetes had minimal effect. Evidence of small vessel disease in the retina increases the likelihood of finding it in the brain. Associations were less prominent in this elderly population than have been described in middle-aged people.
Keywords: Age Factors; Aged; Aged, 80 and over; Arteriosclerosis; Cerebral Infarction; Female; Humans; Leukoaraiosis; Longitudinal Studies; Magnetic Resonance Imaging; Male; Microcirculation; Photography; Retina; Retinal Diseases; Retinal Vessels; Risk Assessment; Risk Factors

Associations of plasma fibrinogen levels with established cardiovascular disease risk factors, inflammatory markers, and other characteristics: individual participant meta-analysis of 154,211 adults in 31 prospective studies: the fibrinogen studies collab - Kaptoge, S; White, I R; Thompson, S G; Wood, A M; Lewington, S; Lowe, G D O; Danesh, J (Am J Epidemiol, 2007)
Long-term increases in plasma fibrinogen levels of 1 g/liter are associated with an approximate doubling of risk of major cardiovascular disease outcomes, but causality remains uncertain. To quantify cross-sectional associations of fibrinogen levels with established risk factors and other characteristics, the investigators combined individual data on 154,211 apparently healthy adults from 31 prospective studies conducted between 1967 and 2003, using a linear mixed model that included random effects at the cohort level. Fibrinogen levels increased with age and showed continuous, approximately linear relations with several risk markers and slightly curvilinear associations with log triglycerides, albumin, and tobacco and alcohol consumption. Female sex, Black ethnicity, lower socioeconomic status, and alcohol abstinence were each associated with modestly higher fibrinogen levels. Approximately one third of the variation in fibrinogen levels was explained by cohort, age, and sex. An additional 7% was explained by established risk factors (notably, positive associations with smoking and body mass index and an inverse association with high density lipoprotein cholesterol), and a further 10% was explained by inflammatory markers (notably, a positive association with C-reactive protein). The association with body mass index was twice as strong in women as in men, whereas the association with smoking was much stronger in men. These findings substantially advance understanding of the correlates and possible determinants of fibrinogen levels.
Keywords: Adult; African Americans; Age Factors; Biomarkers; Body Mass Index; C-Reactive Protein; Cardiovascular Diseases; Cohort Studies; Female; Fibrinogen; Humans; Linear Models; Male; Prospective Studies; Risk Factors; Sex Factors; Smoking; Social Class; United States

Collaborative meta-analysis of individual participant data from observational studies of Lp-PLA2 and cardiovascular diseases. - Ballantyne, C; Cushman, M; Psaty, B; Furberg, C; Khaw, K T; Sandhu, M; Oldgren, J; Rossi, G P; Maiolino, G; Cesari, M; Lenzini, L; James, S K; et al. (Eur J Cardiovasc Prev Rehabil, 2007)
BACKGROUND: A large number of observational epidemiological studies have reported generally positive associations between circulating mass and activity levels of lipoprotein-associated phospholipase A2 (Lp-PLA2) and the risk of cardiovascular diseases. Few studies have been large enough to provide reliable estimates in different circumstances, such as in different subgroups (e.g., by age group, sex, or smoking status) or at different Lp-PLA2 levels. Moreover, most published studies have related disease risk only to baseline values of Lp-PLA2 markers (which can lead to substantial underestimation of any risk relationships because of within-person variability over time) and have used different approaches to adjustment for possible confounding factors. OBJECTIVES: By combination of data from individual participants from all relevant observational studies in a systematic 'meta-analysis', with correction for regression dilution (using available data on serial measurements of Lp-PLA2), the Lp-PLA2 Studies Collaboration will aim to characterize more precisely than has previously been possible the strength and shape of the age and sex-specific associations of plasma Lp-PLA2 with coronary heart disease (and, where data are sufficient, with other vascular diseases, such as ischaemic stroke). It will also help to determine to what extent such associations are independent of possible confounding factors and to explore potential sources of heterogeneity among studies, such as those related to assay methods and study design. It is anticipated that the present collaboration will serve as a framework to investigate related questions on Lp-PLA2 and cardiovascular outcomes. METHODS: A central database is being established containing data on circulating Lp-PLA2 values, sex and other potential confounding factors, age at baseline Lp-PLA2 measurement, age at event or at last follow-up, major vascular morbidity and cause-specific mortality. Information about any repeat measurements of Lp-PLA2 and potential confounding factors has been sought to allow adjustment for possible confounding and correction for regression dilution. The analyses will involve age-specific regression models. Synthesis of the available observational studies of Lp-PLA2 will yield information on a total of about 15 000 cardiovascular disease endpoints.
Keywords: 1-Alkyl-2-acetylglycerophosphocholine Esterase; Cardiovascular Diseases; Humans; Phospholipases A2

Depressive symptoms and age-related macular degeneration in older people: the cardiovascular health study. - Sun, Cong; Tikellis, Gabriella; Klein, Ronald; Steffens, David C; Larsen, Emily K Marino; Wong, Tien Y (Ophthalmic Epidemiol, 2007)
PURPOSE: To examine the association between age-related macular degeneration (AMD) and depressive symptoms. METHODS: Population-based, cross-sectional study. A total of 2,194 persons aged 69-97 years were included in the current analyses. During the 1997-1998 examination, retinal photography from one randomly selected eye was graded for presence of early and late AMD using a modified Wisconsin AMD by Grading System. Depressive symptoms were assessed via a modified version of the Centers for Epidemiologic Studies Depression (CES-D) scale annually from 1989 through 1997-1998. Depressive symptoms were defined as a CES-D score of >9 (top quartile of CES-D score) at the 1997-1998 examination. RESULTS: There were 338 (15.6%) individuals with early AMD and 29 (1.3%) with late AMD. Among them, 368 (16.8%) persons had depressive symptoms at the 1997-1998 examination. Depressive symptoms were not associated with early AMD (multivariable adjusted odds ratio [OR]: 0.97; 95% confidence intervals [CI]: 0.69-1.36) or late AMD (OR: 1.15; 95% CI: 0.38-3.46). Including persons using anti-depressive medications did not alter these associations (OR: 0.98; 95% CI: 0.74-1.32 for early AMD and OR: 0.97; 95% CI: 0.35-2.67 for late AMD). There was no association in multinomial logistic regression models of increasing quartiles of the CES-D scores with early or late AMD status. CONCLUSIONS: Our study did not find an association between early AMD and depressive symptoms in older people.
Keywords: Aged; Aged, 80 and over; Cardiovascular Diseases; Cross-Sectional Studies; Depressive Disorder; Female; Health Surveys; Humans; Intelligence Tests; Macular Degeneration; Male; Photography; United States

The Emerging Risk Factors Collaboration: analysis of individual data on lipid, inflammatory and other markers in over 1.1 million participants in 104 prospective studies of cardiovascular diseases. - Danesh, J; Erqou, S; Walker, M; Thompson, S G; Tipping, R; Ford, C; Pressel, S; Walldius, G; Jungner, I; Folsom, A R; Chambless, L E; Knuiman, M; et al. (Eur J Epidemiol, 2007)
Many long-term prospective studies have reported on associations of cardiovascular diseases with circulating lipid markers and/or inflammatory markers. Studies have not, however, generally been designed to provide reliable estimates under different circumstances and to correct for within-person variability. The Emerging Risk Factors Collaboration has established a central database on over 1.1 million participants from 104 prospective population-based studies, in which subsets have information on lipid and inflammatory markers, other characteristics, as well as major cardiovascular morbidity and cause-specific mortality. Information on repeat measurements on relevant characteristics has been collected in approximately 340,000 participants to enable estimation of and correction for within-person variability. Re-analysis of individual data will yield up to approximately 69,000 incident fatal or nonfatal first ever major cardiovascular outcomes recorded during about 11.7 million person years at risk. The primary analyses will involve age-specific regression models in people without known baseline cardiovascular disease in relation to fatal or nonfatal first ever coronary heart disease outcomes. This initiative will characterize more precisely and in greater detail than has previously been possible the shape and strength of the age- and sex-specific associations of several lipid and inflammatory markers with incident coronary heart disease outcomes (and, secondarily, with other incident cardiovascular outcomes) under a wide range of circumstances. It will, therefore, help to determine to what extent such associations are independent from possible confounding factors and to what extent such markers (separately and in combination) provide incremental predictive value.
Keywords: Albumins; Biomarkers; Cardiovascular Diseases; Databases, Factual; Far East; Humans; Inflammation; Leukocyte Count; Lipids; Lipoproteins, HDL; Prospective Studies; Risk Factors; Triglycerides

Focal atrophy and cerebrovascular disease increase dementia risk among cognitively normal older adults. - Rosano, Caterina; Aizenstein, Howard J; Wu, Minjie; Newman, Anne B; Becker, James T; Lopez, Oscar L; Kuller, Lewis H (J Neuroimaging, 2007)
BACKGROUND AND PURPOSE: This study investigated the association of medial temporal lobe (MTL) atrophy and cerebrovascular disease (white matter hyperintensities [WMH], subclinical infarcts) with the risk of developing Alzheimer's disease (AD) among cognitively normal older adults. METHODS: Risk of developing AD was examined for 155 cognitively normal older adults (77.4 years, 60% women, 81% white). The MTL volumes and the presence of WMH and of subclinical infarcts were determined from brain magnetic resonance imaging (MRI) at the beginning of the study. Follow-up cognitive evaluations (average 4.3 years) identified those who developed AD. RESULTS: The presence of either MTL atrophy or subclinical infarcts was independently and significantly associated with a greater risk to develop AD (OR [95% CI]: 4.4 [1.5, 12.3] and 2.7 [1.0, 7.1], respectively). In addition, those participants with both MTL atrophy and at least one brain infarct had a 7-fold increase in the risk of developing AD (OR [95% CI]: 7.0 [1.5, 33.1]), compared to those who had neither of these conditions. CONCLUSIONS: In cognitively normal older adults, markers of neurodegeneration (as reflected by MTL atrophy) and of cerebrovascular disease (as reflected by infarcts on MRI) independently contribute to the risk to develop AD.
Keywords: Aged; Alzheimer Disease; Analysis of Variance; Atrophy; Cerebrovascular Disorders; Cognition; Female; Humans; Logistic Models; Longitudinal Studies; Magnetic Resonance Imaging; Male; Risk Factors; Temporal Lobe; United States

Frailty and risk of venous thromboembolism in older adults. - Folsom, Aaron R; Boland, Lori L; Cushman, Mary; Heckbert, Susan R; Rosamond, Wayne D; Walston, Jeremy D (J Gerontol A Biol Sci Med Sci, 2007)
BACKGROUND: Frailty is a common risk factor for morbidity and mortality in elderly persons. Recent evidence links frailty to activation of coagulation and inflammatory pathways. We aimed to determine whether frailty in community-dwelling older adults is a risk factor for venous thromboembolism (VTE). METHODS: We conducted a prospective cohort study in four U.S. communities involving 4859 participants 65 years old and older. At baseline, in 1989-1993, we assessed frailty based on weight loss, grip strength, feelings of exhaustion, walk time, and physical activity. Incident VTE (deep vein thrombosis or pulmonary embolus) through 2002 was identified by review of hospital records. RESULTS: Fifty-two percent of the sample was classified as having intermediate or definite frailty. After adjustment for age, race, sex, body mass index, and diabetes, the relative risk of total VTE (n = 150) for people who were frail compared with no frailty was 1.31 (95% confidence interval [CI], 0.93-1.84). The comparably adjusted relative risk for idiopathic VTE (n = 58) was 1.79 (95% CI, 1.02-3.13). CONCLUSIONS: The incidence rates of idiopathic VTE was higher in community-dwelling older adults with baseline frailty compared with no frailty. Further studies of the clotting process in frailty may allow the development of an improved strategy to determine VTE risk in this vulnerable subset of older adults.
Keywords: Age Factors; Aged; Aged, 80 and over; Female; Follow-Up Studies; Frail Elderly; Humans; Male; Morbidity; Motor Activity; Prospective Studies; Risk Factors; Thromboembolism; United States; Venous Thrombosis

Genome-wide association of sleep and circadian phenotypes. - Gottlieb, Daniel J; O'Connor, George T; Wilk, Jemma B (BMC Med Genet, 2007)
BACKGROUND: Numerous studies suggest genetic influences on sleepiness and circadian rhythms. The Sleep Heart Health Study collected questionnaire data on sleep habits and sleepiness from 2848 Framingham Heart Study Offspring Cohort participants. More than 700 participants were genotyped using the Affymetrix 100K SNP GeneChip, providing a unique opportunity to assess genetic linkage and association of these traits. METHODS: Sleepiness (defined as the Epworth Sleepiness Scale score), usual bedtime and usual sleep duration were assessed by self-completion questionnaire. Standardized residual measures adjusted for age, sex and BMI were analyzed. Multipoint variance components linkage analysis was performed. Association of SNPs to sleep phenotypes was analyzed with both population-based and family-based association tests, with analysis limited to 70,987 autosomal SNPs with minor allele frequency > or =10%, call rate > or =80%, and no significant deviation from Hardy-Weinberg equilibrium (p > or = 0.001). RESULTS: Heritability of sleepiness was 0.29, bedtime 0.22, and sleep duration 0.17. Both genotype and sleep phenotype data were available for 749 subjects. Linkage analysis revealed five linkage peaks of LOD >2: four to usual bedtime, one to sleep duration. These peaks include several candidate sleep-related genes, including CSNK2A2, encoding a known component of the circadian molecular clock, and PROK2, encoding a putative transmitter of the behavioral circadian rhythm from the suprachiasmatic nucleus. Association tests identified an association of usual bedtime with a non-synonymous coding SNP in NPSR1 that has been shown to encode a gain of function mutation of the neuropeptide S receptor, whose endogenous ligand is a potent promoter of wakefulness. Each copy of the minor allele of this SNP was associated with a 15 minute later mean bedtime. The lowest p value was for association of sleepiness with a SNP located in an intron of PDE4D, which encodes a cAMP-specific phosphodiesterase widely expressed in human brain. Full association results are posted at http://www.ncbi.nlm.nih.gov/projects/gap/cgi-bin/study.cgi?id=phs000007 webcite. CONCLUSION: This analysis confirms prior reports of significant heritability of sleepiness, usual bedtime, and usual sleep duration. Several genetic loci with suggestive linkage to these traits are identified, including linkage peaks containing circadian clock-related genes. Association tests identify NPSR1 and PDE4D as possible mediators of bedtime and sleepiness.
Keywords: Adult; Alleles; Cardiovascular Diseases; Circadian Rhythm; Cohort Studies; Female; Gene Frequency; Genetic Linkage; Genome, Human; Genotype; Humans; Male; Middle Aged; Phenotype; Polymorphism, Single Nucleotide; Sleep; Surveys and Questionnaires

IL-6 gene variation is associated with IL-6 and C-reactive protein levels but not cardiovascular outcomes in the Cardiovascular Health Study. - Walston, Jeremy D; Fallin, M Daniele; Cushman, Mary; Lange, Leslie; Psaty, Bruce; Jenny, Nancy; Browner, Warren; Tracy, Russell; Durda, Peter; Reiner, Alex (Hum Genet, 2007)
Interleukin-6 (IL-6) and C-reactive protein (CRP) levels increase with age and likely play a role in adverse health outcomes in older adults. The relationship between IL-6 gene tag single nucleotide polymorphisms (SNPs) and circulating IL-6 and CRP levels, cardiovascular disease (CVD) outcomes, and mortality in Caucasian (CA) and African American (AA) participants of the Cardiovascular Health Study (CHS) was evaluated using ANCOVA and Cox proportional hazards models. The minor allele of the promoter SNP 1510 and intronic SNP 3572 associates with significantly higher serum IL-6 and CRP levels in CA but not AA. The CRP association persisted after CA and AA populations were combined and after accounting for multiple comparisons. These associations did not carry through to cardiovascular disease outcomes. Decreased risk of stroke was identified in CA, with the minor allele of SNP 1111 (HRR 0.71, 95% CI 0.52, 0.95), P = 0.02, and increased risk of CVD and all-cause mortality (HRR 1.31, 95% CI 1.05-1.64) in AAs heterozygote for SNP 2989. While genetic variation in the IL-6 gene was associated with circulating IL-6 and especially with CRP concentrations in this study, there is little evidence for association between common IL-6 gene variation and adverse health outcomes in this population of older adults.
Keywords: African Americans; Aged; Alleles; C-Reactive Protein; Cardiovascular Diseases; Cohort Studies; European Continental Ancestry Group; Female; Gene Frequency; Genetic Predisposition to Disease; Genetic Variation; Humans; Interleukin-6; Introns; Longitudinal Studies; Male; Polymorphism, Single Nucleotide; Promoter Regions, Genetic

Insulin resistance and inflammation as precursors of frailty: the Cardiovascular Health Study. - Barzilay, Joshua I; Blaum, Caroline; Moore, Tisha; Xue, Qian Li; Hirsch, Calvin H; Walston, Jeremy D; Fried, Linda P (Arch Intern Med, 2007)
BACKGROUND: Our research group has previously shown that the geriatric syndrome of frailty is associated with features of the metabolic syndrome (MetS) on cross-sectional analysis. METHODS: To test whether MetS and its physiologic determinants-insulin resistance as measured by homeostasis model assessment score (IR-HOMA), increased inflammation and coagulation factor levels, and elevated blood pressure-are associated with incident frailty, we studied a subcohort of participants from the Cardiovascular Health Study observed from 1989/1990 through 1998/1999: 3141 community-dwelling adults, aged 69 to 74 years, without frailty and illnesses that increase inflammation markers or mimic frailty. The association of baseline MetS, IR-HOMA, levels of inflammation and coagulation factors, and systolic blood pressure (SBP) with time to onset of frailty was adjusted for demographic and psychosocial factors and incident events. Our main outcome measure was incident frailty. RESULTS: Metabolic syndrome was not significantly associated with incident frailty (hazard ratio, 1.16 (95% confidence interval [CI], 0.85-1.57). On the other hand, IR-HOMA and C-reactive protein levels were associated with incident frailty: for every standard deviation increment the hazard ratio for frailty was 1.15 (95% CI, 1.02-1.31) and 1.16 (95% CI, 1.02-1.32), respectively. The white blood cell count and factor VIIIc levels had a borderline association. Elevated systolic blood pressure had no association. Similar trends were found for incident prefrailty, a condition that precedes frailty. CONCLUSIONS: Two physiologic components of MetS- IR-HOMA and inflammation-are associated with incident frailty. Based on these results, IR-HOMA can be considered part of a larger process that leads to generalized decline.
Keywords: Aged; Aged, 80 and over; Female; Frail Elderly; Geriatrics; Humans; Inflammation; Insulin Resistance; Male; Metabolic Syndrome; Prospective Studies

Leukocyte telomere length and cardiovascular disease in the cardiovascular health study. - Fitzpatrick, Annette L; Kronmal, Richard A; Gardner, Jeffrey P; Psaty, Bruce M; Jenny, Nancy S; Tracy, Russell P; Walston, Jeremy; Kimura, Masyuki; Aviv, Abraham (Am J Epidemiol, 2007)
The telomere length of replicating somatic cells is inversely correlated with age and has been reported to be associated cross-sectionally with cardiovascular disease (CVD). Leukocyte telomere length, as expressed by mean terminal restriction fragment (TRF) length, was measured in 419 randomly selected participants from the Cardiovascular Health Study, comprising a community-dwelling cohort recruited in four US communities. The authors investigated associations between TRF length and selected measures of subclinical CVD/risk factors for CVD (data were collected at the 1992/1993 clinic visit) and incident CVD (ascertained through June 2002). In these participants (average age = 74.2 years (standard deviation, 5.2)), mean TRF length was 6.3 kilobase pairs (standard deviation, 0.62). Significant or borderline inverse associations were found between TRF length and diabetes, glucose, insulin, diastolic blood pressure, carotid intima-media thickness, and interleukin-6. Associations with body size and C-reactive protein were modified by gender and age, occurring only in men and in participants aged 73 years or younger. In younger (but not older) participants, each shortened kilobase pair of TRF corresponded with a threefold increased risk of myocardial infarction (hazard ratio = 3.08, 95% confidence interval: 1.22, 7.73) and stroke (hazard ratio = 3.22, 95% confidence interval: 1.29, 8.02). These results support the hypotheses that telomere attrition may be related to diseases of aging through mechanisms involving oxidative stress, inflammation, and progression to CVD.
Keywords: Aged; Cardiovascular Diseases; DNA; Female; Humans; Inflammation; Leukocytes; Male; Myocardial Infarction; Oxidative Stress; Pilot Projects; Polymorphism, Restriction Fragment Length; Risk; Risk Assessment; Risk Factors; Telomere

Long-term costs and resource use in elderly participants with congestive heart failure in the Cardiovascular Health Study. - Liao, Lawrence; Anstrom, Kevin J; Gottdiener, John S; Pappas, Paul A; Whellan, David J; Kitzman, Dalane W; Aurigemma, Gerard P; Mark, Daniel B; Schulman, Kevin A; Jollis, James G (Am Heart J, 2007)
BACKGROUND: Although heart failure (HF) afflicts nearly 5 million Americans, the long-term cost of HF care has not been described previously. In a prospective, longitudinal cohort of community-dwelling elderly from 4 regions, we examined the long-term costs and resource use of elderly patients with HF. METHODS: We linked 4860 elderly participants in the National Heart, Lung, and Blood Institute Cardiovascular Health Study to Medicare part A and part B claims from 1992 to 2003. Costs were calculated from Medicare payments and discounted at 3% annually. We applied nonparametric estimators to calculate mean costs and resource use per patient for a 10-year period. To describe the relationship between patient characteristics and long-term costs, we constructed censoring-adjusted regression models. RESULTS: There were 343 participants (84.8% white; 50.1% men; mean age, 78.2 years) with prevalent HF and 4517 participants without HF at study entry. Mean follow-up was 6.7 years (median, 6.4 years). The 10-year survival rates were 33% and 63% for the prevalent HF and nonprevalent HF groups (P < .001), respectively. The mean 10-year medical costs were significantly higher for the prevalent HF cohort (54,704 dollars vs 41 dollars,780, P < .001). The higher costs associated with HF were also reflected in greater resource use with more hospitalizations (P < .05) and more intensive care unit days (P < .05). Participants with HF had more physician visits (P < .05), with most of these encounters involving noncardiology physicians. However, in multivariate models, prevalent HF was not an independent predictor of higher costs. CONCLUSION: Patients with HF consume substantially more health care resources than their elderly peers, and these higher costs persist through 10 years of follow-up. Many of these costs may be related to other comorbid conditions.
Keywords: Aged; Costs and Cost Analysis; Female; Health Resources; Heart Failure; Humans; Male; Medicare; Prospective Studies; Time Factors

Relationship between reported and measured sleep times: the sleep heart health study (SHHS). - Silva, Graciela E; Goodwin, James L; Sherrill, Duane L; Arnold, Jean L; Bootzin, Richard R; Smith, Terry; Walsleben, Joyce A; Baldwin, Carol M; Quan, Stuart F (J Clin Sleep Med, 2007)
STUDY OBJECTIVE: Subjective and objective assessments of sleep may be discrepant due to sleep misperception and measurement effects, the latter of which may change the quality and quantity of a person's usual sleep. This study compared sleep times from polysomnography (PSG) with self-reports of habitual sleep and sleep estimated on the morning after a PSG in adults. DESIGN: Total sleep time and sleep onset latency obtained from unattended home PSGs were compared to sleep times obtained from a questionnaire completed before the PSG and a Morning Survey completed the morning after the PSG. PARTICIPANTS: A total of 2,113 subjects who were > or = 40 years of age were included in this analysis. MEASURES AND RESULTS: Subjects were 53% female, 75% Caucasian, and 38% obese. The mean habitual sleep time (HABTST), morning estimated sleep time (AMTST), and PSG total sleep times (PSGTST) were 422 min, 379 min, and 363 min, respectively. The mean habitual sleep onset latency, morning estimated sleep onset latency, and PSG sleep onset latency were 17.0 min, 21.8 min, and 16.9 min, respectively. Models adjusting for related demographic factors showed that HABTST and AMTST differ significantly from PSGTST by 61 and 18 minutes, respectively. Obese and higher educated people reported less sleep time than their counterparts. Similarly, small but significant differences were seen for sleep latency. CONCLUSIONS: In a community population, self-reported total sleep times and sleep latencies are overestimated even on the morning following overnight PSG.
Keywords: Adult; Attitude to Health; Female; Health Status; Humans; Male; Middle Aged; Polysomnography; Psychometrics; Sleep Initiation and Maintenance Disorders; Sleep Stages; Surveys and Questionnaires; Time Factors; Wakefulness

Retinal microvascular signs, cognitive function, and dementia in older persons: the Cardiovascular Health Study. - Baker, Michelle L; Marino Larsen, Emily K; Kuller, Lewis H; Klein, Ronald; Klein, Barbara E K; Siscovick, David S; Bernick, Charles; Manolio, Teri A; Wong, Tien Yin (Stroke, 2007)
BACKGROUND AND PURPOSE: Cerebral microvascular disease may be a risk factor for the development of dementia in elderly persons. We describe the association of retinal microvascular signs with cognitive function and dementia among older individuals. METHODS: In the population-based Cardiovascular Health Study, 2211 persons aged 69 to 97 years at recruitment had retinal photography. Photographs were evaluated for retinopathy (eg, microaneurysms, retinal hemorrhages), focal arteriolar narrowing, arteriovenous nicking, and retinal arteriolar and venular caliber. Cognitive status was determined from the Digit-Symbol Substitution Test and Modified Mini-Mental State Examination. Participants were also further evaluated for the presence of dementia with detailed neuropsychological testing. Persons with a prior stroke or taking antipsychotic or antidepressant medications were excluded. RESULTS: After adjusting for age, gender, race, field center, education level, internal carotid intima-media thickness, body mass index, hypertension, diabetes, and cigarette smoking status, persons with retinopathy had lower mean Digit-Symbol Substitution Test scores but not Modified Mini-Mental State Examination than those without retinopathy (39 versus 41, P=0.002). In hypertensive persons, retinopathy (multivariable-adjusted OR, 2.10; 95% CI, 1.04 to 4.24) and focal arteriolar narrowing (OR, 3.02; 95% CI, 1.51 to 6.02) were associated with dementia. These associations were not present in individuals without hypertension. CONCLUSIONS: In older persons, our study shows a modest cross-sectional association between retinopathy signs with poorer cognitive function and, in persons with hypertension, with dementia. These data support a possible role of cerebral microvascular disease in the pathogenesis of impaired cognitive function and dementia in older hypertensive persons.
Keywords: Aged; Aged, 80 and over; Cardiovascular Diseases; Cognition; Cross-Sectional Studies; Dementia; Female; Humans; Longitudinal Studies; Male; Microcirculation; Neuropsychological Tests; Retinal Vessels; Risk Factors

Ankle brachial index combined with Framingham Risk Score to predict cardiovascular events and mortality: a meta-analysis. - Fowkes, F G R; Murray, G D; Butcher, I; Heald, C L; Lee, R J; Chambless, L E; Folsom, A R; Hirsch, A T; Dramaix, M; deBacker, G; Wautrecht, J-C; Kornitzer, M; et al. (JAMA, 2008)
CONTEXT: Prediction models to identify healthy individuals at high risk of cardiovascular disease have limited accuracy. A low ankle brachial index (ABI) is an indicator of atherosclerosis and has the potential to improve prediction. OBJECTIVE: To determine if the ABI provides information on the risk of cardiovascular events and mortality independently of the Framingham risk score (FRS) and can improve risk prediction. DATA SOURCES: Relevant studies were identified. A search of MEDLINE (1950 to February 2008) and EMBASE (1980 to February 2008) was conducted using common text words for the term ankle brachial index combined with text words and Medical Subject Headings to capture prospective cohort designs. Review of reference lists and conference proceedings, and correspondence with experts was conducted to identify additional published and unpublished studies. STUDY SELECTION: Studies were included if participants were derived from a general population, ABI was measured at baseline, and individuals were followed up to detect total and cardiovascular mortality. DATA EXTRACTION: Prespecified data on individuals in each selected study were extracted into a combined data set and an individual participant data meta-analysis was conducted on individuals who had no previous history of coronary heart disease. RESULTS: Sixteen population cohort studies fulfilling the inclusion criteria were included. During 480,325 person-years of follow-up of 24,955 men and 23,339 women, the risk of death by ABI had a reverse J-shaped distribution with a normal (low risk) ABI of 1.11 to 1.40. The 10-year cardiovascular mortality in men with a low ABI (< or = 0.90) was 18.7% (95% confidence interval [CI], 13.3%-24.1%) and with normal ABI (1.11-1.40) was 4.4% (95% CI, 3.2%-5.7%) (hazard ratio [HR], 4.2; 95% CI, 3.3-5.4). Corresponding mortalities in women were 12.6% (95% CI, 6.2%-19.0%) and 4.1% (95% CI, 2.2%-6.1%) (HR, 3.5; 95% CI, 2.4-5.1). The HRs remained elevated after adjusting for FRS (2.9 [95% CI, 2.3-3.7] for men vs 3.0 [95% CI, 2.0-4.4] for women). A low ABI (< or = 0.90) was associated with approximately twice the 10-year total mortality, cardiovascular mortality, and major coronary event rate compared with the overall rate in each FRS category. Inclusion of the ABI in cardiovascular risk stratification using the FRS would result in reclassification of the risk category and modification of treatment recommendations in approximately 19% of men and 36% of women. CONCLUSION: Measurement of the ABI may improve the accuracy of cardiovascular risk prediction beyond the FRS.
Keywords: Adult; Age Factors; Aged; Aged, 80 and over; Ankle; Atherosclerosis; Blood Pressure; Brachial Artery; Cardiovascular Diseases; Cohort Studies; Confidence Intervals; Female; Global Health; Humans; Male; Middle Aged; Odds Ratio; Predictive Value of Tests; Risk Assessment; Risk Factors; Severity of Illness Index

Association of restless legs syndrome and cardiovascular disease in the Sleep Heart Health Study. - Winkelman, John W; Shahar, Eyal; Sharief, Imran; Gottlieb, Daniel J (Neurology, 2008)
OBJECTIVE: We evaluated the cross-sectional association between restless legs syndrome (RLS) and prevalent cardiovascular disease (CVD) in a large community-based sample of middle-aged and elderly subjects. METHODS: This is a cross-sectional observational study of 1,559 men and 1,874 women (mean age of 67.9 years) who were enrolled in the Sleep Heart Health Study, a community-based study of the cardiovascular consequences of sleep-disordered breathing. RLS was defined by positive responses on a self-administered questionnaire to the four diagnostic criteria, with symptoms occurring at least five times per month and associated with at least moderate distress. Coronary artery disease (CAD) was determined by self-report of doctor-diagnosed angina, myocardial infarction, or coronary revascularization procedure. Total CVD included CAD or history of physician-diagnosed stroke or heart failure. The relation of RLS to prevalent CAD and CVD was examined by multivariable logistic regression models RESULTS: RLS was present in 6.8% of women (n = 128) and 3.3% of men (n = 51). After adjustment for age, sex, race, body mass index, diabetes mellitus, systolic blood pressure, antihypertensive medication use, total:high-density lipoprotein cholesterol ratio, and smoking history, the ORs for CAD were 2.05 (95% CI 1.38 to 3.04) and for CVD were 2.07 (1.43 to 3.00) for subjects with RLS compared to those without RLS. The associations of RLS with CAD and CVD were stronger in those with RLS symptoms at least 16 times per month and were stronger in those with severe than in those with moderately bothersome symptoms. CONCLUSIONS: Restless legs syndrome (RLS) is associated with prevalent coronary artery disease and cardiovascular disease. This association appears stronger in those with greater frequency or severity of RLS symptoms.
Keywords: Aged; Body Mass Index; Cardiovascular Diseases; Cross-Sectional Studies; Evaluation Studies as Topic; Female; Health Surveys; Humans; Logistic Models; Male; Middle Aged; Odds Ratio; Prevalence; Restless Legs Syndrome; Surveys and Questionnaires

Associations between common fibrinogen gene polymorphisms and cardiovascular disease in older adults. The Cardiovascular Health Study. - Carty, Cara L; Cushman, Mary; Jones, Daniel; Lange, Leslie A; Hindorff, Lucia A; Rice, Kenneth; Jenny, Nancy S; Durda, J Peter; Walston, Jeremy; Carlson, Christopher S; Nickerson, Debbie; Tracy, Russell P; et al. (Thromb Haemost, 2008)
Elevated plasma fibrinogen is a risk factor for cardiovascular disease (CVD), but associations between fibrinogen single nucleotide polymorphisms (SNPs) and disease risk are inconsistent. We investigated whether common (> or = 5% minor allele frequency) variation in the fibrinogen genes (FGA, FGB, FGG) is associated with fibrinogen concentration, carotid artery intima-medial thickness (IMT) and risk of incident myocardial infarction (MI), ischemic stroke and CVD mortality in European- (EA) and African-descent (AA) adults (> or = 65 years) from the Cardiovascular Health Study. TagSNPs were genotyped in 3,969 EA and 719 AA free of MI or stroke at baseline. Race-specific models included multiple testing correction and adjustment for sex, age and site. Among EA, minor alleles of FGA3807, FGB1437 and FGG902 were associated with higher fibrinogen levels; whereas FGA251, FGA2224, FGA6534 and FGG10034 were associated with lower levels, p<0.004 for each. Strongest associations were seen for FGB1437; each additional copy of the minor allele was associated with 13 mg/dl (95%CI: 9-16) higher fibrinogen level. Similar trends in AA were not significant. Fibrinogen haplotypes were not significantly associated with internal or common carotid IMT. No associations with MI or CVD mortality were seen in EA, though FGB1038 and FGG902 were significantly associated with increased and decreased risk of stroke in men, respectively, as were related haplotypes. FGB1038 was also associated with CVD mortality in AA, HR = 1.9 (95%CI: 1.3-2.7). In conclusion, while fibrinogen genetic variation was strongly associated with fibrinogen levels, there was less evidence of association with the more complex outcomes of IMT and CVD events.
Keywords: African Americans; Age Factors; Aged; Brain Ischemia; Cardiovascular Diseases; Carotid Artery Diseases; European Continental Ancestry Group; Female; Fibrinogen; Gene Frequency; Genetic Predisposition to Disease; Haplotypes; Humans; Male; Myocardial Infarction; Polymorphism, Single Nucleotide; Population Surveillance; Proportional Hazards Models; Prospective Studies; Reproducibility of Results; Risk Assessment; Risk Factors; Sex Factors; Stroke; United States

Cardiovascular and mortality risk prediction and stratification using urinary albumin excretion in older adults ages 68-102: the Cardiovascular Health Study. - Cao, Jie J; Biggs, Mary L; Barzilay, Joshua; Konen, Joseph; Psaty, Bruce M; Kuller, Lewis; Bleyer, Anthony J; Olson, Jean; Wexler, Jason; Summerson, John; Cushman, Mary (Atherosclerosis, 2008)
BACKGROUND: Elevated urinary albumin excretion (UAE) is associated with the risk of cardiovascular disease (CVD) and all-cause mortality. We tested the hypothesis that elevated UAE improves cardiovascular risk stratification in an elderly cohort aged 68-102 years. METHODS: We evaluated UAE in 3112 participants of the Cardiovascular Health Study who attended the 1996-1997 examination and had median follow up of 5.4 years. Elevated UAE was defined as urinary albumin to creatinine ratio > or =30 microg/mg. Microalbuminuria and macroalbuminuria were defined as urinary albumin to creatinine ratio 30-300 microg/mg and >300 microg/mg, respectively. Outcomes included CVD (myocardial infarction, stroke, cardiovascular death) and all-cause mortality. Cox proportional hazards models were used to assess the risk of outcomes associated with elevated UAE. RESULTS: The prevalence of elevated UAE was 14.3%, 17.1% and 26.9% in those aged 68-74, 75-84 and 85-102 years, respectively. CVD incidence and all-cause mortality were doubled (7.2% and 8.1% per year) in those with microalbuminuria and tripled (11.1% and 12.3% per year) in those with macroalbuminuria compared to those with normal UAE (3.3% and 3.8% per year). The increased CVD and mortality risks were observed in all age groups after adjustment for conventional risk factors. The adjusted population attributable risk percent of CVD and all-cause mortality for elevated UAE was 11% and 12%, respectively. When participants were cross-classified by UAE and Framingham Risk Score categories, the 5-year cumulative incidence of coronary heart disease among participants with elevated UAE and a 5-year predicted risk of 5-10% was 20%, substantially higher than 6.3% in those with UAE <30m microg/mg. CONCLUSION: Elevated UAE was associated with an increased risk of CVD and all-cause mortality in all age groups from 68 to 102 years. Combining elevated UAE with the Framingham risk scores may improve risk stratification for CVD in the elderly.
Keywords: Aged; Aged, 80 and over; Albuminuria; Biomarkers; Cohort Studies; Coronary Disease; Cross-Sectional Studies; Female; Health Surveys; Humans; Male; Predictive Value of Tests; Risk

Chronic kidney disease increases risk for venous thromboembolism. - Wattanakit, Keattiyoat; Cushman, Mary; Stehman-Breen, Catherine; Heckbert, Susan R; Folsom, Aaron R (J Am Soc Nephrol, 2008)
Chronic kidney disease (CKD) is associated with increased risk for cardiovascular disease morbidity and mortality, but its association with incident venous thromboembolism (VTE) in non-dialysis-dependent patients has not been evaluated in a community-based population. With the use of data from the Longitudinal Investigation of Thromboembolism Etiology (LITE) study, 19,073 middle-aged and elderly adults were categorized on the basis of estimated GFR, and cystatin C (available in 4734 participants) was divided into quintiles. During a mean follow-up time of 11.8 yr, 413 participants developed VTE. Compared with participants with normal kidney function, relative risk for VTE was 1.28 (95% confidence interval [CI] 1.02 to 1.59) for those with mildly decreased kidney function and 2.09 (95% CI 1.47 to 2.96) for those with stage 3/4 CKD, when adjusted for age, gender, race, and center. After additional adjustment for cardiovascular disease risk factors, an increased risk for VTE was still observed in participants with stage 3/4 CKD, with a multivariable adjusted relative risk of 1.71 (95% CI 1.18 to 2.49). There was no significant association between cystatin C and VTE. In conclusion, middle-aged and elderly patients with CKD (stages 3 through 4) are at increased risk for incident VTE, suggesting that VTE prophylaxis may be particularly important in this population.
Keywords: Aged; Aged, 80 and over; Body Mass Index; Diabetic Nephropathies; Factor VIII; Female; Glomerular Filtration Rate; Humans; Hypertension; Kidney Failure, Chronic; Longitudinal Studies; Male; Middle Aged; Risk Factors; Thromboembolism; Venous Thrombosis

Common variants in the CRP gene in relation to longevity and cause-specific mortality in older adults: the Cardiovascular Health Study. - Hindorff, Lucia A; Rice, Kenneth M; Lange, Leslie A; Diehr, Paula; Halder, Indrani; Walston, Jeremy; Kwok, Pui; Ziv, Elad; Nievergelt, Caroline; Cummings, Steven R; Newman, Anne B; Tracy, Russell P; et al. (Atherosclerosis, 2008)
Common polymorphisms in the CRP gene are associated with plasma CRP levels in population-based studies, but associations with age-related events are uncertain. A previous study of CRP haplotypes in older adults was broadened to include longevity and cause-specific mortality (all-cause, noncardiovascular (non-CV), and cardiovascular (CV)). Common haplotypes were inferred from four tagSNPs in 4512 whites and five tagSNPs in 812 blacks from the Cardiovascular Health Study, a longitudinal cohort of adults over age 65. Exploratory analyses addressed early versus late mortality. CRP haplotypes were not associated with all-cause mortality or longevity overall in either population, but associations with all-cause mortality differed during early and late periods. In blacks, the haplotype tagged by 3872A (rs1205) was associated with increased risk of non-CV mortality, relative to other haplotypes (adjusted hazard ratio for each additional copy: 1.42, 95% CI: 1.07, 1.87). Relative to other haplotypes, this haplotype was associated with decreased risk of early but not decreased risk of late CV mortality in blacks; among whites, a haplotype tagged by 2667C (rs1800947) gave similar but nonsignificant findings. If confirmed, CRP genetic variants may be weakly associated with CV and non-CV mortality in older adults, particularly in self-identified blacks.
Keywords: African Americans; Aged; C-Reactive Protein; Cardiovascular Diseases; Cause of Death; Cohort Studies; Female; Genetic Predisposition to Disease; Haplotypes; Humans; Linear Models; Longevity; Male; Polymorphism, Single Nucleotide; Proportional Hazards Models; United States

Inflammatory markers and longitudinal lung function decline in the elderly. - Jiang, Rui; Burke, Gregory L; Enright, Paul L; Newman, Anne B; Margolis, Helene G; Cushman, Mary; Tracy, Russell P; Wang, Yuanjia; Kronmal, Richard A; Barr, R Graham (Am J Epidemiol, 2008)
Longitudinal studies examining associations of the inflammatory markers fibrinogen and C-reactive protein (CRP) with lung function decline are sparse. The authors examined whether elevated fibrinogen and CRP levels were associated with greater longitudinal lung function decline in the elderly. The Cardiovascular Health Study measured fibrinogen and CRP in 5,790 Whites and African Americans from four US communities aged 65 years or older in 1989-1990 or 1992-1993. Spirometry was performed in 1989-1990 and 4, 7, and 16 years later. Fibrinogen and CRP were inversely associated with lung function at baseline after adjustment for multiple potential confounders. In mixed models, the rate of decline in forced expiratory volume in 1 second (FEV(1))/forced vital capacity (FVC) ratio with increasing age was faster among those with higher baseline fibrinogen (-0.032%/year per standard deviation higher fibrinogen (95% confidence interval: -0.057, -0.0074)) but not among those with higher CRP (-0.0037%/year per standard deviation higher CRP (95% confidence interval: -0.013, 0.0056)). Longitudinal analyses for FEV(1) and FVC yielded results in the direction opposite of that hypothesized, possibly because of the high mortality rate and strong inverse association of FEV(1) and FVC but not FEV(1)/FVC with mortality. An alternative approach to missing data yielded similar results. In conclusion, higher levels of fibrinogen, but not CRP, independently predicted greater FEV(1)/FVC decline in the elderly.
Keywords: Aged; C-Reactive Protein; Cross-Sectional Studies; Female; Fibrinogen; Forced Expiratory Volume; Geriatric Assessment; Humans; Logistic Models; Longitudinal Studies; Lung Volume Measurements; Male; Multicenter Studies as Topic; Pulmonary Disease, Chronic Obstructive; Spirometry

Insulin-like growth factors, their binding proteins, and prostate cancer risk: analysis of individual patient data from 12 prospective studies. - Roddam, Andrew W; Allen, Naomi E; Appleby, Paul; Key, Timothy J; Ferrucci, Luigi; Carter, H Ballentine; Metter, E Jeffrey; Chen, Chu; Weiss, Noel S; Fitzpatrick, Annette; Hsing, Ann W; Lacey, James V; et al. (Ann Intern Med, 2008)
BACKGROUND: Some, but not all, published results have shown an association between circulating blood levels of some insulin-like growth factors (IGFs) and their binding proteins (IGFBPs) and the subsequent risk for prostate cancer. PURPOSE: To assess the association between levels of IGFs and IGFBPs and the subsequent risk for prostate cancer. DATA SOURCES: Studies identified in PubMed, Web of Science, and CancerLit. STUDY SELECTION: The principal investigators of all studies that published data on circulating concentrations of sex steroids, IGFs, or IGFBPs and prostate cancer risk using prospectively collected blood samples were invited to collaborate. DATA EXTRACTION: Investigators provided individual participant data on circulating concentrations of IGF-I, IGF-II, IGFBP-II, and IGFBP-III and participant characteristics to a central data set in Oxford, United Kingdom. DATA SYNTHESIS: The study included data on 3700 men with prostate cancer and 5200 control participants. On average, case patients were 61.5 years of age at blood collection and received a diagnosis of prostate cancer 5 years after blood collection. The greater the serum IGF-I concentration, the greater the subsequent risk for prostate cancer (odds ratio [OR] in the highest vs. lowest quintile, 1.38 [95% CI, 1.19 to 1.60]; P < 0.001 for trend). Neither IGF-II nor IGFBP-II concentrations were associated with prostate cancer risk, but statistical power was limited. Insulin-like growth factor I and IGFBP-III were correlated (r = 0.58), and although IGFBP-III concentration seemed to be associated with prostate cancer risk, this was secondary to its association with IGF-I levels. Insulin-like growth factor I concentrations seemed to be more positively associated with low-grade than high-grade disease; otherwise, the association between IGFs and IGFBPs and prostate cancer risk had no statistically significant heterogeneity related to stage or grade of disease, time between blood collection and diagnosis, age and year of diagnosis, prostate-specific antigen level at recruitment, body mass index, smoking, or alcohol intake. LIMITATIONS: Insulin-like growth factor concentrations were measured in only 1 sample for each participant, and the laboratory methods to measure IGFs differed in each study. Not all patients had disease stage or grade information, and the diagnosis of prostate cancer may differ among the studies. CONCLUSION: High circulating IGF-I concentrations are associated with a moderately increased risk for prostate cancer.
Keywords: Aged; Humans; Insulin-Like Growth Factor Binding Protein 2; Insulin-Like Growth Factor Binding Protein 3; Insulin-Like Growth Factor Binding Proteins; Insulin-Like Growth Factor I; Insulin-Like Growth Factor II; Male; Middle Aged; Prospective Studies; Prostatic Neoplasms; Risk Factors; Somatomedins

No advantage of A beta 42-lowering NSAIDs for prevention of Alzheimer dementia in six pooled cohort studies. - Szekely, C A; Green, R C; Breitner, J C S; Østbye, T; Beiser, A S; Corrada, M M; Dodge, H H; Ganguli, M; Kawas, C H; Kuller, L H; Psaty, B M; Resnick, S M; et al. (Neurology, 2008)
INTRODUCTION: Observational studies show reduced incidence of Alzheimer dementia (AD) in users of nonsteroidal anti-inflammatory drugs (NSAIDs). One hypothesis holds that the subset of NSAIDs known as selective A beta(42)-lowering agents (SALAs) is responsible for this apparent reduction in AD risk. METHODS: We pooled individual-level data from six prospective studies to obtain a sufficient sample to examine AD risk in users of SALA vs non-SALA NSAIDs. RESULTS: Of 13,499 initially dementia-free participants (70,863 person-years), 820 developed incident AD. Users of NSAIDs (29.6%) showed reduced risk of AD (adjusted hazard ratio [aHR] 0.77, 95% CI 0.65-0.91). The point estimates were similar for SALAs (aHR 0.87, CI 0.72-1.04) and non-SALAs (aHR 0.75, CI 0.56-1.01). Because 573 NSAID users (14.5%) reported taking both a SALA and non-SALA, we examined their use alone and in combination. Resulting aHRs were 0.82 (CI 0.67-0.99) for SALA only, 0.60 (CI 0.40-0.90) for non-SALA only, and 0.87 (CI 0.57-1.33) for both NSAIDs (Wald test for differences, p = 0.32). The 40.7% of participants who used aspirin also showed reduced risk of AD, even when they used no other NSAIDs (aHR 0.78, CI 0.66-0.92). By contrast, there was no association with use of acetaminophen (aHR 0.93, CI 0.76-1.13). CONCLUSIONS: In this pooled dataset, nonsteroidal anti-inflammatory drug (NSAID) use reduced the risk of Alzheimer dementia (AD). However, there was no apparent advantage in AD risk reduction for the subset of NSAIDs shown to selectively lower A beta(42), suggesting that all conventional NSAIDs including aspirin have a similar protective effect in humans.
Keywords: Acetaminophen; Adolescent; Adult; Aged; Aged, 80 and over; Alzheimer Disease; Amyloid beta-Peptides; Analgesics, Non-Narcotic; Anti-Inflammatory Agents, Non-Steroidal; Aspirin; Cohort Studies; Female; Humans; Male; Middle Aged; Neuroprotective Agents; Peptide Fragments; Proportional Hazards Models; Prospective Studies; Risk Factors

Polymorphisms of the HNF1A gene encoding hepatocyte nuclear factor-1 alpha are associated with C-reactive protein. - Reiner, Alexander P; Barber, Mathew J; Guan, Yongtao; Ridker, Paul M; Lange, Leslie A; Chasman, Daniel I; Walston, Jeremy D; Cooper, Gregory M; Jenny, Nancy S; Rieder, Mark J; Durda, J Peter; Smith, Joshua D; et al. (Am J Hum Genet, 2008)
Data from the Pharmacogenomics and Risk of Cardiovascular Disease (PARC) study and the Cardiovascular Health Study (CHS) provide independent and confirmatory evidence for association between common polymorphisms of the HNF1A gene encoding hepatocyte nuclear factor-1 alpha and plasma C-reactive protein (CRP) concentration. Analyses with the use of imputation-based methods to combine genotype data from both studies and to test untyped SNPs from the HapMap database identified several SNPs within a 5 kb region of HNF1A intron 1 with the strongest evidence of association with CRP phenotype.
Keywords: Aged; Bayes Theorem; C-Reactive Protein; Female; Hepatocyte Nuclear Factor 1-alpha; Humans; Hydroxymethylglutaryl-CoA Reductase Inhibitors; Male; Middle Aged; Polymorphism, Single Nucleotide; Pravastatin; Simvastatin

Relation of sleep-disordered breathing to carotid plaque and intima-media thickness. - Wattanakit, Keattiyoat; Boland, Lori; Punjabi, Naresh M; Shahar, Eyal (Atherosclerosis, 2008)
BACKGROUND: Sleep-disordered breathing (SDB) is associated with clinical cardiovascular disease (CVD), but its relation to subclinical atherosclerosis remains to be determined. METHODS: We analyzed the cross-sectional associations of SDB, measured by the respiratory disturbance index (RDI), a hypoxemia index, and an arousal index, with carotid plaque and carotid intima-media thickness (IMT), measured by ultrasound. The sample included 985 participants in the Sleep Heart Health Study (mean age-62, median RDI-8.7) with no history of coronary heart disease and stroke, of whom 396 had evidence of a carotid plaque. RESULTS: As compared with the first quartile of the RDI (0-1.2), the crude odds ratio for carotid plaque was 1.14, 1.27, and 1.48 for the second (1.3-4.1), third (4.2-10.7), and fourth (>10.7) quartile, respectively. After adjustment for CVD risk factors, the corresponding odds ratios were reduced (1.00, 1.04, 1.07, and 1.25). Similarly, the unadjusted mean carotid IMT increased with RDI, but adjusted means (mm) were similar (0.84, 0.85, 0.84, 0.85). Spline regression models did not show monotonicity of the dose-response functions at the right end of the RDI distribution. Neither the hypoxemia index nor the arousal index was associated with carotid plaque or carotid IMT. CONCLUSION: The results of this study suggest that crude, positive associations between SDB and subclinical atherosclerosis can be attributed to confounding by CVD risk factors.
Keywords: Aged; Carotid Arteries; Carotid Artery Diseases; Female; Humans; Male; Middle Aged; Odds Ratio; Risk Factors; Sleep Apnea Syndromes; Tunica Intima; Tunica Media; Ultrasonography

Age-related macular degeneration and risk of coronary heart disease and stroke: the Cardiovascular Health Study. - Sun, Cong; Klein, Ronald; Wong, Tien Y (Ophthalmology, 2009)
PURPOSE: To examine the associations of age-related macular degeneration (AMD) with incident coronary heart disease (CHD) and stroke in the Cardiovascular Health Study. DESIGN: Population-based prospective cohort study. PARTICIPANTS: A total of 1786 white and African-American participants free of CHD or 2228 participants free of stroke, aged 69 to 97 years. METHODS: AMD was evaluated from photographs taken in 1997 and 1998. MAIN OUTCOME MEASURES: Incident CHD and stroke ascertained using standardized methods. RESULTS: Of the 1786 persons free of CHD, 303 developed incident CHD over 7 years. Participants with early AMD (n = 277) had a higher cumulative incidence of CHD than participants without early AMD (25.8% vs. 18.9%, P = 0.001). By adjusting for age, gender, race, systolic and diastolic blood pressure, hypertension status, fasting glucose, triglyceride, low-density lipoprotein cholesterol, cigarette smoking, pack years of smoking, and C-reactive protein, the presence of early AMD was associated with an increased risk of incident CHD (hazard ratio 1.57; 95% confidence interval, 1.17-2.22). Late AMD (n = 25) was not associated with incident CHD (hazard ratio 0.78; 95% confidence interval, 0.25-2.48). Among 2228 persons at risk, 198 developed incident stroke; neither early nor late AMD was associated with incident stroke. CONCLUSIONS: This study suggests persons with early AMD have a higher risk of CHD but not stroke in a population aged 69 to 97 years. This provides further support that AMD is associated with underlying systemic vascular disease.
Keywords: African Americans; Age Factors; Aged; Aged, 80 and over; Blood Pressure; Cholesterol, LDL; Coronary Disease; European Continental Ancestry Group; Female; Humans; Incidence; Macular Degeneration; Male; Prospective Studies; Risk Factors; Sex Factors; Stroke; Triglycerides; United States

Angiotensin-converting enzyme inhibitors and cognitive decline in older adults with hypertension: results from the Cardiovascular Health Study. - Sink, Kaycee M; Leng, Xiaoyan; Williamson, Jeff; Kritchevsky, Stephen B; Yaffe, Kristine; Kuller, Lewis; Yasar, Sevil; Atkinson, Hal; Robbins, Mike; Psaty, Bruce; Goff, David C (Arch Intern Med, 2009)
BACKGROUND: Hypertension (HTN) is a risk factor for dementia, and animal studies suggest that centrally active angiotensin-converting enzyme (ACE) inhibitors (those that cross the blood-brain barrier) may protect against dementia beyond HTN control. METHODS: Participants in the Cardiovascular Health Study Cognition Substudy with treated HTN and no diagnosis of congestive heart failure (n = 1054; mean age, 75 years) were followed up for a median of 6 years to determine whether cumulative exposure to ACE inhibitors (as a class and by central activity), compared with other anti-HTN agents, was associated with a lower risk of incident dementia, cognitive decline (by Modified Mini-Mental State Examination [3MSE]), or incident disability in instrumental activities of daily living (IADLs). RESULTS: Among 414 participants who were exposed to ACE inhibitors and 640 who were not, there were 158 cases of incident dementia. Compared with other anti-HTN drugs, there was no association between exposure to all ACE inhibitors and risk of dementia (hazard ratio [HR], 1.01; 95% confidence interval [CI], 0.88-1.15), difference in 3MSE scores (-0.32 points per year; P = .15), or odds of disability in IADLs (odds ratio [OR], 1.06; 95% CI, 0.99-1.14). Adjusted results were similar. However, centrally active ACE inhibitors were associated with 65% less decline in 3MSE scores per year of exposure (P = .01), and noncentrally active ACE inhibitors were associated with a greater risk of incident dementia (adjusted HR, 1.20; 95% CI, 1.00-1.43 per year of exposure) and greater odds of disability in IADLs (adjusted OR, 1.16; 95% CI, 1.03-1.30 per year of exposure) compared with other anti-HTN drugs. CONCLUSIONS: While ACE inhibitors as a class do not appear to be independently associated with dementia risk or cognitive decline in older hypertensive adults, there may be within-class differences in regard to these outcomes. These results should be confirmed with a randomized clinical trial of a centrally active ACE inhibitor in the prevention of cognitive decline and dementia.
Keywords: Aged; Angiotensin-Converting Enzyme Inhibitors; Blood-Brain Barrier; Cognition; Dementia; Female; Follow-Up Studies; Humans; Hypertension; Incidence; Male; Prospective Studies; Risk Factors

Association of novel genetic Loci with circulating fibrinogen levels: a genome-wide association study in 6 population-based cohorts. - Dehghan, Abbas; Yang, Qiong; Peters, Annette; Basu, Saonli; Bis, Joshua C; Rudnicka, Alicja R; Kavousi, Maryam; Chen, Ming-Huei; Baumert, Jens; Lowe, Gordon D O; McKnight, Barbara; Tang, Weihong; et al. (Circ Cardiovasc Genet, 2009)
BACKGROUND: Fibrinogen is both central to blood coagulation and an acute-phase reactant. We aimed to identify common variants influencing circulation fibrinogen levels. METHODS AND RESULTS: We conducted a genome-wide association analysis on 6 population-based studies, the Rotterdam Study, the Framingham Heart Study, the Cardiovascular Health Study, the Atherosclerosis Risk in Communities Study, the Monitoring of Trends and Determinants in Cardiovascular Disease/KORA Augsburg Study, and the British 1958 Birth Cohort Study, including 22 096 participants of European ancestry. Four loci were marked by 1 or more single-nucleotide polymorphisms that demonstrated genome-wide significance (P<5.0 x 10(-8)). These included a single-nucleotide polymorphism located in the fibrinogen beta chain (FGB) gene and 3 single-nucleotide polymorphisms representing newly identified loci. The high-signal single-nucleotide polymorphisms were rs1800789 in exon 7 of FGB (P=1.8 x 10(-30)), rs2522056 downstream from the interferon regulatory factor 1 (IRF1) gene (P=1.3 x 10(-15)), rs511154 within intron 1 of the propionyl coenzyme A carboxylase (PCCB) gene (P=5.9 x 10(-10)), and rs1539019 on the NLR family pyrin domain containing 3 isoforms (NLRP3) gene (P=1.04 x 10(-8)). CONCLUSIONS: Our findings highlight biological pathways that may be important in regulation of inflammation underlying cardiovascular disease.
Keywords: Adult; Aged; Aged, 80 and over; Cardiovascular Diseases; Cohort Studies; European Continental Ancestry Group; Female; Fibrinogen; Genetic Loci; Genome-Wide Association Study; Humans; Male; Middle Aged; Pedigree; Polymorphism, Single Nucleotide; Young Adult

Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) Consortium: Design of prospective meta-analyses of genome-wide association studies from 5 cohorts. - Psaty, Bruce M; O'Donnell, Christopher J; Gudnason, Vilmundur; Lunetta, Kathryn L; Folsom, Aaron R; Rotter, Jerome I; Uitterlinden, André G; Harris, Tamara B; Witteman, Jacqueline C M; Boerwinkle, Eric (Circ Cardiovasc Genet, 2009)
BACKGROUND: The primary aim of genome-wide association studies is to identify novel genetic loci associated with interindividual variation in the levels of risk factors, the degree of subclinical disease, or the risk of clinical disease. The requirement for large sample sizes and the importance of replication have served as powerful incentives for scientific collaboration. Methods- The Cohorts for Heart and Aging Research in Genomic Epidemiology Consortium was formed to facilitate genome-wide association studies meta-analyses and replication opportunities among multiple large population-based cohort studies, which collect data in a standardized fashion and represent the preferred method for estimating disease incidence. The design of the Cohorts for Heart and Aging Research in Genomic Epidemiology Consortium includes 5 prospective cohort studies from the United States and Europe: the Age, Gene/Environment Susceptibility-Reykjavik Study, the Atherosclerosis Risk in Communities Study, the Cardiovascular Health Study, the Framingham Heart Study, and the Rotterdam Study. With genome-wide data on a total of about 38 000 individuals, these cohort studies have a large number of health-related phenotypes measured in similar ways. For each harmonized trait, within-cohort genome-wide association study analyses are combined by meta-analysis. A prospective meta-analysis of data from all 5 cohorts, with a properly selected level of genome-wide statistical significance, is a powerful approach to finding genuine phenotypic associations with novel genetic loci. CONCLUSIONS: The Cohorts for Heart and Aging Research in Genomic Epidemiology Consortium and collaborating non-member studies or consortia provide an excellent framework for the identification of the genetic determinants of risk factors, subclinical-disease measures, and clinical events.
Keywords: Adult; Aged; Aging; Cohort Studies; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Genotype; Heart Diseases; Humans; Male; Meta-Analysis as Topic; Middle Aged; Phenotype; Research Design; Risk Factors

Common coding variants of the HNF1A gene are associated with multiple cardiovascular risk phenotypes in community-based samples of younger and older European-American adults: the Coronary Artery Risk Development in Young Adults Study and The Cardiovascula - Reiner, Alexander P; Gross, Myron D; Carlson, Christopher S; Bielinski, Suzette J; Lange, Leslie A; Fornage, Myriam; Jenny, Nancy S; Walston, Jeremy; Tracy, Russell P; Williams, O Dale; Jacobs, David R; Nickerson, Deborah A (Circ Cardiovasc Genet, 2009)
BACKGROUND: The transcription factor hepatocyte nuclear factor (HNF)-1 alpha regulates the activity of a number of genes involved in innate immunity, blood coagulation, lipid and glucose transport and metabolism, and cellular detoxification. Common polymorphisms of the HNF-1 alpha gene (HNF1A) were recently associated with plasma C-reactive protein and gamma-glutamyl transferase concentration in middle-aged to older European Americans (EA). METHODS AND RESULTS: We assessed whether common variants of HNF1A are associated with C-reactive protein, gamma-glutamyl transferase, and other atherosclerotic and metabolic risk factors, in the large, population-based Coronary Artery Risk Development in Young Adults Study of healthy young EA (n=2154) and African American (AA; n=2083) adults. The minor alleles of Ile27Leu (rs1169288) and Ser486Asn (rs2464196) were associated with 0.10 to 0.15 standard deviation units lower C-reactive protein and gamma-glutamyl transferase levels in EA. The same HNF1A coding variants were associated with higher low-density lipoprotein cholesterol, apolipoprotein B, creatinine, and fibrinogen in EA. We replicated the associations between HNF1A coding variants and C-reactive protein, fibrinogen, low-density lipoprotein cholesterol, and renal function in a second population-based sample of EA adults 65 years and older from the Cardiovascular Health Study. The HNF1A Ser486Asn and/or Ile27Leu variants were also associated with increased risk of subclinical coronary atherosclerosis in Coronary Artery Risk Development in Young Adults and with incident coronary heart disease in Cardiovascular Health Study. The Ile27Leu and Ser486Asn variants were 3-fold less common in AA than in EA. There was little evidence of association between HNF1A genotype and atherosclerosis-related phenotypes in AA. CONCLUSIONS: Common polymorphisms of HNF1A seem to influence multiple phenotypes related to cardiovascular risk in the general population of younger and older EA adults.
Keywords: Adolescent; Adult; African Americans; Aged; Aged, 80 and over; C-Reactive Protein; Cardiovascular Diseases; Cholesterol, LDL; Cohort Studies; European Continental Ancestry Group; Female; Fibrinogen; gamma-Glutamyltransferase; Genetic Predisposition to Disease; Genotype; Hepatocyte Nuclear Factor 1-alpha; Humans; Male; Middle Aged; Phenotype; Polymorphism, Single Nucleotide; Risk Factors

Common variants at ten loci influence QT interval duration in the QTGEN Study. - Newton-Cheh, Christopher; Eijgelsheim, Mark; Rice, Kenneth M; de Bakker, Paul I W; Yin, Xiaoyan; Estrada, Karol; Bis, Joshua C; Marciante, Kristin; Rivadeneira, Fernando; Noseworthy, Peter A; Sotoodehnia, Nona; Smith, Nicholas L; et al. (Nat Genet, 2009)
QT interval duration, reflecting myocardial repolarization on the electrocardiogram, is a heritable risk factor for sudden cardiac death and drug-induced arrhythmias. We conducted a meta-analysis of three genome-wide association studies in 13,685 individuals of European ancestry from the Framingham Heart Study, the Rotterdam Study and the Cardiovascular Health Study, as part of the QTGEN consortium. We observed associations at P < 5 x 10(-8) with variants in NOS1AP, KCNQ1, KCNE1, KCNH2 and SCN5A, known to be involved in myocardial repolarization and mendelian long-QT syndromes. Associations were found at five newly identified loci, including 16q21 near NDRG4 and GINS3, 6q22 near PLN, 1p36 near RNF207, 16p13 near LITAF and 17q12 near LIG3 and RFFL. Collectively, the 14 independent variants at these 10 loci explain 5.4-6.5% of the variation in QT interval. These results, together with an accompanying paper, offer insights into myocardial repolarization and suggest candidate genes that could predispose to sudden cardiac death and drug-induced arrhythmias.
Keywords: Adaptor Proteins, Signal Transducing; Adult; Aged; Arrhythmias, Cardiac; Chromosome Mapping; Death, Sudden, Cardiac; Electroencephalography; ERG1 Potassium Channel; Ether-A-Go-Go Potassium Channels; European Continental Ancestry Group; Genetic Predisposition to Disease; Genetic Variation; Genome, Human; Humans; KCNQ1 Potassium Channel; Meta-Analysis as Topic; Muscle Proteins; NAV1.5 Voltage-Gated Sodium Channel; Polymorphism, Single Nucleotide; Potassium Channels, Voltage-Gated; Risk Factors; Sodium Channels

Early age-related macular degeneration, cognitive function, and dementia: the Cardiovascular Health Study. - Baker, Michelle L; Wang, Jie Jin; Rogers, Sophie; Klein, Ronald; Kuller, Lewis H; Larsen, Emily K; Wong, Tien Yin (Arch Ophthalmol, 2009)
OBJECTIVE: To describe the association of cognitive function and dementia with early age-related macular degeneration (AMD) in older individuals. METHODS: This population-based study included 2,088 persons aged 69 to 97 years who participated in the Cardiovascular Health Study. The AMD was assessed from retinal photographs based on a modified Wisconsin AMD grading system. Cognitive function was assessed using the Digit Symbol Substitution Test (DSST) and the Modified Mini-Mental State Examination. Participants were also evaluated for dementia using detailed neuropsychological testing. RESULTS: After controlling for age, sex, race, and study center, persons with low DSST scores (lowest quartile of scores, < or =30) were more likely to have early AMD (odds ratio, 1.38; 95% confidence interval, 1.03-1.85) than were persons with higher DSST scores. In analyses further controlling for education, systolic blood pressure, total cholesterol level, diabetes mellitus, smoking status, and apolipoprotein E genotype, this association was stronger (odds ratio, 2.00; 95% confidence interval, 1.29-3.10). There was no association of low Modified Mini-Mental State Examination scores, dementia, or Alzheimer disease with early AMD. CONCLUSIONS: In this older population, cognitive impairment may share common age-related pathogenesis and risk factors with early AMD.
Keywords: Aged; Aged, 80 and over; Cardiovascular Diseases; Cognition Disorders; Dementia; Female; Humans; Intelligence Tests; Macular Degeneration; Male; Neuropsychological Tests; Odds Ratio; Prospective Studies; Risk Factors; United States

Genetic variants associated with cardiac structure and function: a meta-analysis and replication of genome-wide association data. - Vasan, Ramachandran S; Glazer, Nicole L; Felix, Janine F; Lieb, Wolfgang; Wild, Philipp S; Felix, Stephan B; Watzinger, Norbert; Larson, Martin G; Smith, Nicholas L; Dehghan, Abbas; Grosshennig, Anika; Schillert, Arne; et al. (JAMA, 2009)
CONTEXT: Echocardiographic measures of left ventricular (LV) structure and function are heritable phenotypes of cardiovascular disease. OBJECTIVE: To identify common genetic variants associated with cardiac structure and function by conducting a meta-analysis of genome-wide association data in 5 population-based cohort studies (stage 1) with replication (stage 2) in 2 other community-based samples. DESIGN, SETTING, AND PARTICIPANTS: Within each of 5 community-based cohorts comprising the EchoGen consortium (stage 1; n = 12 612 individuals of European ancestry; 55% women, aged 26-95 years; examinations between 1978-2008), we estimated the association between approximately 2.5 million single-nucleotide polymorphisms (SNPs; imputed to the HapMap CEU panel) and echocardiographic traits. In stage 2, SNPs significantly associated with traits in stage 1 were tested for association in 2 other cohorts (n = 4094 people of European ancestry). Using a prespecified P value threshold of 5 x 10(-7) to indicate genome-wide significance, we performed an inverse variance-weighted fixed-effects meta-analysis of genome-wide association data from each cohort. MAIN OUTCOME MEASURES: Echocardiographic traits: LV mass, internal dimensions, wall thickness, systolic dysfunction, aortic root, and left atrial size. RESULTS: In stage 1, 16 genetic loci were associated with 5 echocardiographic traits: 1 each with LV internal dimensions and systolic dysfunction, 3 each with LV mass and wall thickness, and 8 with aortic root size. In stage 2, 5 loci replicated (6q22 locus associated with LV diastolic dimensions, explaining <1% of trait variance; 5q23, 12p12, 12q14, and 17p13 associated with aortic root size, explaining 1%-3% of trait variance). CONCLUSIONS: We identified 5 genetic loci harboring common variants that were associated with variation in LV diastolic dimensions and aortic root size, but such findings explained a very small proportion of variance. Further studies are required to replicate these findings, identify the causal variants at or near these loci, characterize their functional significance, and determine whether they are related to overt cardiovascular disease.
Keywords: Adult; Aged; Aged, 80 and over; Aorta; Cardiovascular Diseases; Echocardiography; European Continental Ancestry Group; Female; Genome-Wide Association Study; Genotype; Heart Atria; Heart Ventricles; Humans; Male; Middle Aged; Organ Size; Phenotype; Polymorphism, Single Nucleotide; Risk Factors; Ventricular Dysfunction, Left; Ventricular Function, Left

Genomewide association studies of stroke. - Ikram, M Arfan; Seshadri, Sudha; Bis, Joshua C; Fornage, Myriam; DeStefano, Anita L; Aulchenko, Yurii S; Debette, Stephanie; Lumley, Thomas; Folsom, Aaron R; van den Herik, Evita G; Bos, Michiel J; Beiser, Alexa; et al. (N Engl J Med, 2009)
BACKGROUND: The genes underlying the risk of stroke in the general population remain undetermined. METHODS: We carried out an analysis of genomewide association data generated from four large cohorts composing the Cohorts for Heart and Aging Research in Genomic Epidemiology consortium, including 19,602 white persons (mean [+/-SD] age, 63+/-8 years) in whom 1544 incident strokes (1164 ischemic strokes) developed over an average follow-up of 11 years. We tested the markers most strongly associated with stroke in a replication cohort of 2430 black persons with 215 incident strokes (191 ischemic strokes), another cohort of 574 black persons with 85 incident strokes (68 ischemic strokes), and 652 Dutch persons with ischemic stroke and 3613 unaffected persons. RESULTS: Two intergenic single-nucleotide polymorphisms on chromosome 12p13 and within 11 kb of the gene NINJ2 were associated with stroke (P<5x10(-8)). NINJ2 encodes an adhesion molecule expressed in glia and shows increased expression after nerve injury. Direct genotyping showed that rs12425791 was associated with an increased risk of total (i.e., all types) and ischemic stroke, with hazard ratios of 1.30 (95% confidence interval [CI], 1.19 to 1.42) and 1.33 (95% CI, 1.21 to 1.47), respectively, yielding population attributable risks of 11% and 12% in the discovery cohorts. Corresponding hazard ratios were 1.35 (95% CI, 1.01 to 1.79; P=0.04) and 1.42 (95% CI, 1.06 to 1.91; P=0.02) in the large cohort of black persons and 1.17 (95% CI, 1.01 to 1.37; P=0.03) and 1.19 (95% CI, 1.01 to 1.41; P=0.04) in the Dutch sample; the results of an underpowered analysis of the smaller black cohort were nonsignificant. CONCLUSIONS: A genetic locus on chromosome 12p13 is associated with an increased risk of stroke.
Keywords: African Continental Ancestry Group; Aged; Chromosomes, Human, Pair 12; Cohort Studies; European Continental Ancestry Group; Female; Genetic Markers; Genetic Predisposition to Disease; Genome-Wide Association Study; Genotype; Humans; Male; Middle Aged; Polymorphism, Single Nucleotide; Proportional Hazards Models; Risk Factors; Stroke

Genome-wide association study of blood pressure and hypertension. - Levy, Daniel; Ehret, Georg B; Rice, Kenneth; Verwoert, Germaine C; Launer, Lenore J; Dehghan, Abbas; Glazer, Nicole L; Morrison, Alanna C; Johnson, Andrew D; Aspelund, Thor; Aulchenko, Yurii; Lumley, Thomas; et al. (Nat Genet, 2009)
Blood pressure is a major cardiovascular disease risk factor. To date, few variants associated with interindividual blood pressure variation have been identified and replicated. Here we report results of a genome-wide association study of systolic (SBP) and diastolic (DBP) blood pressure and hypertension in the CHARGE Consortium (n = 29,136), identifying 13 SNPs for SBP, 20 for DBP and 10 for hypertension at P < 4 × 10(-7). The top ten loci for SBP and DBP were incorporated into a risk score; mean BP and prevalence of hypertension increased in relation to the number of risk alleles carried. When ten CHARGE SNPs for each trait were included in a joint meta-analysis with the Global BPgen Consortium (n = 34,433), four CHARGE loci attained genome-wide significance (P < 5 × 10(-8)) for SBP (ATP2B1, CYP17A1, PLEKHA7, SH2B3), six for DBP (ATP2B1, CACNB2, CSK-ULK3, SH2B3, TBX3-TBX5, ULK4) and one for hypertension (ATP2B1). Identifying genes associated with blood pressure advances our understanding of blood pressure regulation and highlights potential drug targets for the prevention or treatment of hypertension.
Keywords: Blood Pressure; Cell Line; Chromosome Mapping; Chromosomes, Human; Diastole; Gene Expression Regulation; Genetic Association Studies; Genome-Wide Association Study; Humans; Hypertension; Liver; Lymphocytes; Meta-Analysis as Topic; Odds Ratio; Phenotype; Prevalence; Risk Assessment; Systole

Higher serum testosterone concentration in older women is associated with insulin resistance, metabolic syndrome, and cardiovascular disease. - Patel, Shrita M; Ratcliffe, Sarah J; Reilly, Muredach P; Weinstein, Rachel; Bhasin, Shalender; Blackman, Marc R; Cauley, Jane A; Sutton-Tyrrell, Kim; Robbins, John; Fried, Linda P; Cappola, Anne R (J Clin Endocrinol Metab, 2009)
CONTEXT: Early postmenopausal women with higher testosterone (T) levels have increased insulin resistance (IR) and cardiovascular risk factors, but whether this translates into increased cardiovascular disease later in life is unknown. OBJECTIVE: The objective of the study was to determine whether higher T levels are associated with IR, the metabolic syndrome (MetSyn), and coronary heart disease (CHD) in elderly women. DESIGN: Total T and free T by equilibrium dialysis were measured using ultrasensitive assays in 344 women aged 65-98 yr enrolled in the Cardiovascular Health Study. Cross-sectional analyses were performed to examine the associations between total and free T and IR, MetSyn, and CHD. RESULTS: There was a stepwise increase in the homeostasis model assessment of insulin resistance with increasing total (P = 0.0.003) and free T (P = 0.02) level and a corresponding decrease in Quantitative Insulin Sensitivity Check Index (P < 0.001 and P = 0.002, respectively). In adjusted models, higher levels of both total and free T were strongly associated with abdominal obesity and high fasting glucose, the two MetSyn components most strongly linked to IR. After adjustment, women in the top quartile of total T levels had a 3-fold greater odds of MetSyn (odds ratio 3.15, 95% confidence interval 1.57-6.35) than those in the bottom quartile and a 3-fold greater odds of CHD (odds ratio 2.95, 95% confidence interval 1.2-7.3) than those in second quartile, whereas free T was not significantly associated with MetSyn or CHD. CONCLUSIONS: Higher levels of T are associated with IR, MetSyn, and CHD in elderly women. Whether T is a marker or mediator of cardiovascular disease in this population merits further investigation.
Keywords: Aged; Aged, 80 and over; Blood Glucose; Cardiovascular Diseases; Coronary Disease; Female; Humans; Insulin; Insulin Resistance; Metabolic Syndrome; Odds Ratio; Radioimmunoassay; Socioeconomic Factors; Testosterone; Treatment Outcome

Hypertension genes and retinal vascular calibre: the Cardiovascular Health Study. - Sun, C; Wang, J J; Islam, F M; Heckbert, S R; Klein, R; Siscovick, D S; Klein, B E K; Wong, T Y (J Hum Hypertens, 2009)
We examined the associations of single nucleotide polymorphisms (SNPs) in three candidate hypertension genes, alpha-adducin (ADD1/G460W), beta2-adrenergic receptor (ADRB2/Arg16Gly and Gln27Glu) and G-protein beta3 subunit (GNB3/C825T), with retinal arteriolar calibre (an intermediate marker of chronic hypertension) and venular calibre. Data in 1842 participants (1554 whites and 288 African Americans) aged 69-96 years from the Cardiovascular Health Study with genotype and retinal vascular calibre data were included. A computer-assisted method was used to measure retinal vascular calibre. We analysed four SNPs and multilocus interaction for three genes. All SNPs were in Hardy-Weinberg equilibrium in whites and African Americans. The study had sufficient power to detect 0.5% of the total variance of retinal vascular calibre contributed by each SNP in the total population, except for the GNB3 gene variant. No significant associations between these SNPs in the genes studied and mean retinal arteriolar and venular calibre were found in single-gene or multilocus analysis (for example, age-, gender-, race-adjusted mean retinal arteriolar calibre was similar between participants who were ADD1/460W homozygotes and ADD1/G allele carriers, 166.2 vs 167.7 microm). In conclusion, this study found no evidence of an association of SNPs in candidate hypertension genes studied here with retinal vascular calibre.
Keywords: African Americans; Aged; Aged, 80 and over; Arterioles; Calmodulin-Binding Proteins; European Continental Ancestry Group; Heterotrimeric GTP-Binding Proteins; Humans; Hypertension; Longitudinal Studies; Polymorphism, Single Nucleotide; Receptors, Adrenergic, beta-2; Retinal Vessels

Inflammation and stress-related candidate genes, plasma interleukin-6 levels, and longevity in older adults. - Walston, Jeremy D; Matteini, Amy M; Nievergelt, Caroline; Lange, Leslie A; Fallin, Dani M; Barzilai, Nir; Ziv, Elad; Pawlikowska, Ludmila; Kwok, Pui; Cummings, Steve R; Kooperberg, Charles; LaCroix, Andrea; et al. (Exp Gerontol, 2009)
Interleukin-6 (IL-6) is an inflammatory cytokine that influences the development of inflammatory and aging-related disorders and ultimately longevity. In order to study the influence of variants in genes that regulate inflammatory response on IL-6 levels and longevity, we screened a panel of 477 tag SNPs across 87 candidate genes in >5000 older participants from the population-based Cardiovascular Health Study (CHS). Baseline plasma IL-6 concentration was first confirmed as a strong predictor of all-cause mortality. Functional alleles of the IL6R and PARP1 genes were significantly associated with 15%-20% higher baseline IL-6 concentration per copy among CHS European-American (EA) participants (all p<10(-4)). In a case/control analysis nested within this EA cohort, the minor allele of PARP1 rs1805415 was nominally associated with decreased longevity (p=0.001), but there was no evidence of association between IL6R genotype and longevity. The PARP1 rs1805415--longevity association was subsequently replicated in one of two independent case/control studies. In a pooled analysis of all three studies, the "risk" of longevity associated with the minor allele of PARP1 rs1805415 was 0.79 (95%CI 0.62-1.02; p=0.07). These findings warrant further study of the potential role of PARP1 genotype in inflammatory and aging-related phenotypes.
Keywords: Aged; Aged, 80 and over; Aging; Cardiovascular Diseases; Case-Control Studies; Female; Genetic Variation; Genotype; Humans; Inflammation; Interleukin-6; Longevity; Male; Phenotype; Poly (ADP-Ribose) Polymerase-1; Poly(ADP-ribose) Polymerases; Risk Factors

Lipoprotein(a) concentration and the risk of coronary heart disease, stroke, and nonvascular mortality. - Erqou, Sebhat; Kaptoge, Stephen; Perry, Philip L; Di Angelantonio, Emanuele; Thompson, Alexander; White, Ian R; Marcovina, Santica M; Collins, Rory; Thompson, Simon G; Danesh, John (JAMA, 2009)
CONTEXT: Circulating concentration of lipoprotein(a) (Lp[a]), a large glycoprotein attached to a low-density lipoprotein-like particle, may be associated with risk of coronary heart disease (CHD) and stroke. OBJECTIVE: To assess the relationship of Lp(a) concentration with risk of major vascular and nonvascular outcomes. STUDY SELECTION: Long-term prospective studies that recorded Lp(a) concentration and subsequent major vascular morbidity and/or cause-specific mortality published between January 1970 and March 2009 were identified through electronic searches of MEDLINE and other databases, manual searches of reference lists, and discussion with collaborators. DATA EXTRACTION: Individual records were provided for each of 126,634 participants in 36 prospective studies. During 1.3 million person-years of follow-up, 22,076 first-ever fatal or nonfatal vascular disease outcomes or nonvascular deaths were recorded, including 9336 CHD outcomes, 1903 ischemic strokes, 338 hemorrhagic strokes, 751 unclassified strokes, 1091 other vascular deaths, 8114 nonvascular deaths, and 242 deaths of unknown cause. Within-study regression analyses were adjusted for within-person variation and combined using meta-analysis. Analyses excluded participants with known preexisting CHD or stroke at baseline. DATA SYNTHESIS: Lipoprotein(a) concentration was weakly correlated with several conventional vascular risk factors and it was highly consistent within individuals over several years. Associations of Lp(a) with CHD risk were broadly continuous in shape. In the 24 cohort studies, the rates of CHD in the top and bottom thirds of baseline Lp(a) distributions, respectively, were 5.6 (95% confidence interval [CI], 5.4-5.9) per 1000 person-years and 4.4 (95% CI, 4.2-4.6) per 1000 person-years. The risk ratio for CHD, adjusted for age and sex only, was 1.16 (95% CI, 1.11-1.22) per 3.5-fold higher usual Lp(a) concentration (ie, per 1 SD), and it was 1.13 (95% CI, 1.09-1.18) following further adjustment for lipids and other conventional risk factors. The corresponding adjusted risk ratios were 1.10 (95% CI, 1.02-1.18) for ischemic stroke, 1.01 (95% CI, 0.98-1.05) for the aggregate of nonvascular mortality, 1.00 (95% CI, 0.97-1.04) for cancer deaths, and 1.00 (95% CI, 0.95-1.06) for nonvascular deaths other than cancer. CONCLUSION: Under a wide range of circumstances, there are continuous, independent, and modest associations of Lp(a) concentration with risk of CHD and stroke that appear exclusive to vascular outcomes.
Keywords: Cause of Death; Coronary Disease; Humans; Lipoprotein(a); Risk Factors; Stroke

Meta-analysis: retinal vessel caliber and risk for coronary heart disease. - McGeechan, Kevin; Liew, Gerald; Macaskill, Petra; Irwig, Les; Klein, Ronald; Klein, Barbara E K; Wang, Jie Jin; Mitchell, Paul; Vingerling, Johannes R; Dejong, Paulus T V M; Witteman, Jacqueline C M; Breteler, Monique M B; et al. (Ann Intern Med, 2009)
BACKGROUND: Retinal vessel caliber may be a novel marker of coronary heart disease (CHD) risk. However, the sex-specific effect, magnitude of association, and effect independent of traditional CHD disease risk factors remain unclear. PURPOSE: To determine the association between retinal vessel caliber and risk for CHD. DATA SOURCES: Relevant studies in any language identified through MEDLINE (1950 to June 2009) and EMBASE (1950 to June 2009) databases. STUDY SELECTION: Studies were included if they examined a general population, measured retinal vessel caliber from retinal photographs, and documented CHD risk factors and incident CHD events. DATA EXTRACTION: 6 population-based prospective cohort studies provided data for individual participant meta-analysis. DATA SYNTHESIS: Proportional hazards models, adjusted for traditional CHD risk factors, were constructed for retinal vessel caliber and incident CHD in women and men. Among 22,159 participants who were free of CHD and followed for 5 to 14 years, 2219 (10.0%) incident CHD events occurred. Retinal vessel caliber changes (wider venules and narrower arterioles) were each associated with an increased risk for CHD in women (pooled multivariable-adjusted hazard ratios, 1.16 [95% CI, 1.06 to 1.26] per 20-microm increase in venular caliber and 1.17 [CI, 1.07 to 1.28] per 20-microm decrease in arteriolar caliber) but not in men (1.02 [CI, 0.94 to 1.10] per 20-microm increase in venular caliber and 1.02 [CI, 0.95 to 1.10] per 20-microm decrease in arteriolar caliber). Women without hypertension or diabetes had higher hazard ratios. LIMITATION: Error in the measurement of retinal vessel caliber and Framingham variables was not taken into account. CONCLUSION: Retinal vessel caliber changes were independently associated with an increased risk for CHD events in women.
Keywords: Adult; Aged; Arterioles; Biomarkers; Coronary Disease; Female; Humans; Male; Middle Aged; Proportional Hazards Models; Retinal Vessels; Risk Factors; Sex Factors; Venules

Multiple loci associated with indices of renal function and chronic kidney disease. - Köttgen, Anna; Glazer, Nicole L; Dehghan, Abbas; Hwang, Shih-Jen; Katz, Ronit; Li, Man; Yang, Qiong; Gudnason, Vilmundur; Launer, Lenore J; Harris, Tamara B; Smith, Albert V; Arking, Dan E; et al. (Nat Genet, 2009)
Chronic kidney disease (CKD) has a heritable component and is an important global public health problem because of its high prevalence and morbidity. We conducted genome-wide association studies (GWAS) to identify susceptibility loci for glomerular filtration rate, estimated by serum creatinine (eGFRcrea) and cystatin C (eGFRcys), and CKD (eGFRcrea < 60 ml/min/1.73 m(2)) in European-ancestry participants of four population-based cohorts (ARIC, CHS, FHS, RS; n = 19,877; 2,388 CKD cases), and tested for replication in 21,466 participants (1,932 CKD cases). We identified significant SNP associations (P < 5 × 10(-8)) with CKD at the UMOD locus, with eGFRcrea at UMOD, SHROOM3 and GATM-SPATA5L1, and with eGFRcys at CST and STC1. UMOD encodes the most common protein in human urine, Tamm-Horsfall protein, and rare mutations in UMOD cause mendelian forms of kidney disease. Our findings provide new insights into CKD pathogenesis and underscore the importance of common genetic variants influencing renal function and disease.
Keywords: Chromosome Mapping; Cohort Studies; Genetic Variation; Genome-Wide Association Study; Glomerular Filtration Rate; Humans; Kidney; Kidney Failure, Chronic; Meta-Analysis as Topic; Mucoproteins; Netherlands; Polymorphism, Single Nucleotide; Prevalence; Uromodulin

Multiple loci influence erythrocyte phenotypes in the CHARGE Consortium. - Ganesh, Santhi K; Zakai, Neil A; van Rooij, Frank J A; Soranzo, Nicole; Smith, Albert V; Nalls, Michael A; Chen, Ming-Huei; Köttgen, Anna; Glazer, Nicole L; Dehghan, Abbas; Kuhnel, Brigitte; Aspelund, Thor; et al. (Nat Genet, 2009)
Measurements of erythrocytes within the blood are important clinical traits and can indicate various hematological disorders. We report here genome-wide association studies (GWAS) for six erythrocyte traits, including hemoglobin concentration (Hb), hematocrit (Hct), mean corpuscular volume (MCV), mean corpuscular hemoglobin (MCH), mean corpuscular hemoglobin concentration (MCHC) and red blood cell count (RBC). We performed an initial GWAS in cohorts of the CHARGE Consortium totaling 24,167 individuals of European ancestry and replication in additional independent cohorts of the HaemGen Consortium totaling 9,456 individuals. We identified 23 loci significantly associated with these traits in a meta-analysis of the discovery and replication cohorts (combined P values ranging from 5 x 10(-8) to 7 x 10(-86)). Our findings include loci previously associated with these traits (HBS1L-MYB, HFE, TMPRSS6, TFR2, SPTA1) as well as new associations (EPO, TFRC, SH2B3 and 15 other loci). This study has identified new determinants of erythrocyte traits, offering insight into common variants underlying variation in erythrocyte measures.
Keywords: Blood Pressure; Cell Line; Cohort Studies; Endothelial Cells; Erythrocytes; Gene Expression; Genome, Human; Genome-Wide Association Study; Humans; Hypertension; Phenotype; Polymorphism, Single Nucleotide; Quantitative Trait Loci

NRXN3 is a novel locus for waist circumference: a genome-wide association study from the CHARGE Consortium. - Heard-Costa, Nancy L; Zillikens, M Carola; Monda, Keri L; Johansson, Asa; Harris, Tamara B; Fu, Mao; Haritunians, Talin; Feitosa, Mary F; Aspelund, Thor; Eiriksdottir, Gudny; Garcia, Melissa; Launer, Lenore J; et al. (PLoS Genet, 2009)
Central abdominal fat is a strong risk factor for diabetes and cardiovascular disease. To identify common variants influencing central abdominal fat, we conducted a two-stage genome-wide association analysis for waist circumference (WC). In total, three loci reached genome-wide significance. In stage 1, 31,373 individuals of Caucasian descent from eight cohort studies confirmed the role of FTO and MC4R and identified one novel locus associated with WC in the neurexin 3 gene [NRXN3 (rs10146997, p = 6.4x10(-7))]. The association with NRXN3 was confirmed in stage 2 by combining stage 1 results with those from 38,641 participants in the GIANT consortium (p = 0.009 in GIANT only, p = 5.3x10(-8) for combined analysis, n = 70,014). Mean WC increase per copy of the G allele was 0.0498 z-score units (0.65 cm). This SNP was also associated with body mass index (BMI) [p = 7.4x10(-6), 0.024 z-score units (0.10 kg/m(2)) per copy of the G allele] and the risk of obesity (odds ratio 1.13, 95% CI 1.07-1.19; p = 3.2x10(-5) per copy of the G allele). The NRXN3 gene has been previously implicated in addiction and reward behavior, lending further evidence that common forms of obesity may be a central nervous system-mediated disorder. Our findings establish that common variants in NRXN3 are associated with WC, BMI, and obesity.
Keywords: Aged; Body Mass Index; Cohort Studies; European Continental Ancestry Group; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Male; Middle Aged; Nerve Tissue Proteins; Obesity; Polymorphism, Single Nucleotide; Waist Circumference

Polysomnographic and health-related quality of life correlates of restless legs syndrome in the Sleep Heart Health Study. - Winkelman, John W; Redline, Susan; Baldwin, Carol M; Resnick, Helaine E; Newman, Anne B; Gottlieb, Daniel J (Sleep, 2009)
STUDY OBJECTIVES: Sleep disturbance is the primary clinical morbidity of restless legs syndrome (RLS). To date, sleep disturbance in RLS has been measured in (1) clinical samples with polysomnography (PSG) or (2) population-based samples by self-report. The objective of this study was to analyze sleep by PSG in a population-based sample with symptoms of RLS. DESIGN: Cross-sectional observational study. SETTING: Community-based. PARTICIPANTS: 3433 older men and women. INTERVENTIONS: None. MEASUREMENTS AND RESULTS: RLS was evaluated using an 8-item self-administered questionnaire based on NIH diagnostic criteria and required symptoms occurring > or = five times per month and associated with at least moderate distress. Health-related quality of life (HRQOL) was determined using the SF-36. Unattended, in-home PSG was performed. Data were assessed using general linear models with adjustment for demographic, health-related variables, and apnea-hypopnea index (AHI). Subjects with RLS had longer adjusted mean sleep latency (39.8 vs 26.4 min, P < 0.0001) and higher arousal index (20.1 vs 18.0, P = 0.0145) than those without RLS. Sleep latency increased progressively as the frequency of RLS symptoms increased from 5-15 days per month to 6-7 days per week. No differences in sleep stage percentages were observed between participants with and without RLS. Subjects with RLS also reported poorer HRQOL in all physical domains as well as in the Mental Health and Vitality domains. CONCLUSIONS: These novel PSG data from a nonclinical, community-based sample of individuals with RLS document sleep disturbance in the home even in individuals with intermittent symptoms.
Keywords: Adult; Aged; Cohort Studies; Comorbidity; Cross-Sectional Studies; Female; Humans; Male; Middle Aged; Polysomnography; Prospective Studies; Quality of Life; Restless Legs Syndrome; Sleep Initiation and Maintenance Disorders; Statistics as Topic

Predicting risk of dementia in older adults: The late-life dementia risk index. - Barnes, D E; Covinsky, K E; Whitmer, R A; Kuller, L H; Lopez, O L; Yaffe, K (Neurology, 2009)
OBJECTIVE: To develop a late-life dementia risk index that can accurately stratify older adults into those with a low, moderate, or high risk of developing dementia within 6 years. METHODS: Subjects were 3,375 participants in the Cardiovascular Health Cognition Study without evidence of dementia at baseline. We used logistic regression to identify those factors most predictive of developing incident dementia within 6 years and developed a point system based on the logistic regression coefficients. RESULTS: Subjects had a mean age of 76 years at baseline; 59% were women and 15% were African American. Fourteen percent (n = 480) developed dementia within 6 years. The final late-life dementia risk index included older age (1-2 points), poor cognitive test performance (2-4 points), body mass index <18.5 (2 points), > or =1 apolipoprotein E epsilon4 alleles (1 point), cerebral MRI findings of white matter disease (1 point) or ventricular enlargement (1 point), internal carotid artery thickening on ultrasound (1 point), history of bypass surgery (1 point), slow physical performance (1 point), and lack of alcohol consumption (1 point) (c statistic, 0.81; 95% confidence interval, 0.79-0.83). Four percent of subjects with low scores developed dementia over 6 years compared with 23% of subjects with moderate scores and 56% of subjects with high scores. CONCLUSIONS: The late-life dementia risk index accurately stratified older adults into those with low, moderate, and high risk of developing dementia. This tool could be used in clinical or research settings to target prevention and intervention strategies toward high-risk individuals.
Keywords: Age Factors; Aged; Aged, 80 and over; Alcohol Drinking; Apolipoprotein E4; Body Mass Index; Carotid Stenosis; Cerebrum; Cognition Disorders; Cohort Studies; Coronary Artery Bypass; Dementia; Female; Genetic Markers; Health Status Indicators; Humans; Logistic Models; Male; Predictive Value of Tests; Risk Assessment; Risk Factors; Risk Reduction Behavior

Prediction of incident stroke events based on retinal vessel caliber: a systematic review and individual-participant meta-analysis. - McGeechan, Kevin; Liew, Gerald; Macaskill, Petra; Irwig, Les; Klein, Ronald; Klein, Barbara E K; Wang, Jie Jin; Mitchell, Paul; Vingerling, Johannes R; de Jong, Paulus T V M; Witteman, Jacqueline C M; Breteler, Monique M B; et al. (Am J Epidemiol, 2009)
The caliber of the retinal vessels has been shown to be associated with stroke events. However, the consistency and magnitude of association, and the changes in predicted risk independent of traditional risk factors, are unclear. To determine the association between retinal vessel caliber and the risk of stroke events, the investigators combined individual data from 20,798 people, who were free of stroke at baseline, in 6 cohort studies identified from a search of the Medline (National Library of Medicine, Bethesda, Maryland) and EMBASE (Elsevier B.V., Amsterdam, the Netherlands) databases. During follow-up of 5-12 years, 945 (4.5%) incident stroke events were recorded. Wider retinal venular caliber predicted stroke (pooled hazard ratio = 1.15, 95% confidence interval: 1.05, 1.25 per 20-micron increase in caliber), but the caliber of retinal arterioles was not associated with stroke (pooled hazard ratio = 1.00, 95% confidence interval: 0.92, 1.08). There was weak evidence of heterogeneity in the hazard ratio for retinal venular caliber, which may be attributable to differences in follow-up strategies across studies. Inclusion of retinal venular caliber in prediction models containing traditional stroke risk factors reassigned 10.1% of people at intermediate risk into different, mostly lower, risk categories.
Keywords: Aged; Fluorescein Angiography; Humans; Middle Aged; Predictive Value of Tests; Proportional Hazards Models; Retinal Artery; Retinal Vein; Retinal Vessels; Risk Factors; Stroke

Race, gender, and mortality in adults > or =65 years of age with incident heart failure (from the Cardiovascular Health Study). - Parashar, Susmita; Katz, Ronit; Smith, Nicholas L; Arnold, Alice M; Vaccarino, Viola; Wenger, Nanette K; Gottdiener, John S (Am J Cardiol, 2009)
In patients with heart failure (HF), mortality is lower in women versus men. However, it is unknown whether the survival advantage in women compared with men is present in both whites and African Americans with HF. The inception cohort consisted of adults > or =65 years with incident HF after enrollment in the CHS, a prospective population-based study of cardiovascular disease. Of 5,888 CHS subjects, 1,264 developed new HF and were followed up for 3 years. Subjects were categorized into 4 race-gender groups, and Cox proportional hazard regression models were used to examine whether 3-year total and cardiovascular mortality differed among the 4 groups after adjusting for sociodemographic factors, co-morbidities, and treatment. A gender-race interaction was also tested for each outcome. In subjects with incident HF, African Americans had more hypertension and diabetes than whites, and white men had more coronary heart disease than other gender-race groups. Receipt of cardiovascular treatments among the 4 groups was similar. Mortality rates after HF were lower in women compared with men (for white women, African-American women, African-American men, and white men, total mortality was 35.5, 33.6, 44.4, and 40.5/100 person-years, and cardiovascular mortality was 18.4, 19.5, 20.2, and 22.7/100 person-years, respectively). After adjusting for covariates, women had a 15% to 20% lower risk of total and cardiovascular mortality compared with men, but there was no significant difference in outcome by race. The gender-race interaction for either outcome was not significant. In conclusion, in older adults with HF, women had significantly better survival than men irrespective of race, suggesting that gender-based survival differences may be more important than race-based differences.
Keywords: African Americans; Age Factors; Aged; Aged, 80 and over; Cohort Studies; Continental Population Groups; European Continental Ancestry Group; Female; Heart Failure; Humans; Incidence; Male; Proportional Hazards Models; Sex Factors; United States

Replication of findings on the association of genetic variation in 24 hemostasis genes and risk of incident venous thrombosis. - Smith, N L; Wiggins, K L; Reiner, A P; Lange, L A; Cushman, M; Heckbert, S R; Lumley, T; Rice, K M; Folsom, A R; Psaty, B M (J Thromb Haemost, 2009)
Keywords: Adolescent; Adult; Aged; Aged, 80 and over; Case-Control Studies; Cohort Studies; Female; Genetic Association Studies; Genetic Predisposition to Disease; Genetic Variation; Haplotypes; Hemostasis; Humans; Incidence; Male; Menopause; Middle Aged; Polymorphism, Single Nucleotide; Reproducibility of Results; Risk; Thrombophilia; Venous Thrombosis; Young Adult

Systematically missing confounders in individual participant data meta-analysis of observational cohort studies. - Jackson, Dan; White, Ian; Kostis, J B; Wilson, A C; Folsom, A R; Wu, K; Chambless, L; Benderly, M; Goldbourt, U; Willeit, J; Kiechl, S; Yarnell, J W G; et al. (Stat Med, 2009)
One difficulty in performing meta-analyses of observational cohort studies is that the availability of confounders may vary between cohorts, so that some cohorts provide fully adjusted analyses while others only provide partially adjusted analyses. Commonly, analyses of the association between an exposure and disease either are restricted to cohorts with full confounder information, or use all cohorts but do not fully adjust for confounding. We propose using a bivariate random-effects meta-analysis model to use information from all available cohorts while still adjusting for all the potential confounders. Our method uses both the fully adjusted and the partially adjusted estimated effects in the cohorts with full confounder information, together with an estimate of their within-cohort correlation. The method is applied to estimate the association between fibrinogen level and coronary heart disease incidence using data from 154,012 participants in 31 cohorts
Keywords: Cohort Studies; Computer Simulation; Coronary Disease; Data Interpretation, Statistical; Female; Fibrinogen; Humans; Male; Meta-Analysis as Topic; Models, Statistical

Variants in ZFHX3 are associated with atrial fibrillation in individuals of European ancestry. - Benjamin, Emelia J; Rice, Kenneth M; Arking, Dan E; Pfeufer, Arne; van Noord, Charlotte; Smith, Albert V; Schnabel, Renate B; Bis, Joshua C; Boerwinkle, Eric; Sinner, Moritz F; Dehghan, Abbas; Lubitz, Steven A; et al. (Nat Genet, 2009)
We conducted meta-analyses of genome-wide association studies for atrial fibrillation (AF) in participants from five community-based cohorts. Meta-analyses of 896 prevalent (15,768 referents) and 2,517 incident (21,337 referents) AF cases identified a new locus for AF (ZFHX3, rs2106261, risk ratio RR = 1.19; P = 2.3 x 10(-7)). We replicated this association in an independent cohort from the German AF Network (odds ratio = 1.44; P = 1.6 x 10(-11); combined RR = 1.25; combined P = 1.8 x 10(-15)).
Keywords: Atrial Fibrillation; Chromosomes, Human, Pair 16; European Continental Ancestry Group; Genetic Predisposition to Disease; Genome-Wide Association Study; Homeodomain Proteins; Humans; Meta-Analysis as Topic; Mutation; Polymorphism, Single Nucleotide; Reproducibility of Results

Association analyses of 249,796 individuals reveal 18 new loci associated with body mass index. - Speliotes, Elizabeth K; Willer, Cristen J; Berndt, Sonja I; Monda, Keri L; Thorleifsson, Gudmar; Jackson, Anne U; Lango Allen, Hana; Lindgren, Cecilia M; Luan, Jian'an; Mägi, Reedik; Randall, Joshua C; Vedantam, Sailaja; et al. (Nat Genet, 2010)
Obesity is globally prevalent and highly heritable, but its underlying genetic factors remain largely elusive. To identify genetic loci for obesity susceptibility, we examined associations between body mass index and ∼ 2.8 million SNPs in up to 123,865 individuals with targeted follow up of 42 SNPs in up to 125,931 additional individuals. We confirmed 14 known obesity susceptibility loci and identified 18 new loci associated with body mass index (P < 5 × 10⁻⁸), one of which includes a copy number variant near GPRC5B. Some loci (at MC4R, POMC, SH2B1 and BDNF) map near key hypothalamic regulators of energy balance, and one of these loci is near GIPR, an incretin receptor. Furthermore, genes in other newly associated loci may provide new insights into human body weight regulation.
Keywords: Body Height; Body Mass Index; Body Size; Body Weight; Chromosome Mapping; European Continental Ancestry Group; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Obesity; Polymorphism, Single Nucleotide

Association of genome-wide variation with the risk of incident heart failure in adults of European and African ancestry: a prospective meta-analysis from the cohorts for heart and aging research in genomic epidemiology (CHARGE) consortium. - Smith, Nicholas L; Felix, Janine F; Morrison, Alanna C; Demissie, Serkalem; Glazer, Nicole L; Loehr, Laura R; Cupples, L Adrienne; Dehghan, Abbas; Lumley, Thomas; Rosamond, Wayne D; Lieb, Wolfgang; Rivadeneira, Fernando; et al. (Circ Cardiovasc Genet, 2010)
BACKGROUND: Although genetic factors contribute to the onset of heart failure (HF), no large-scale genome-wide investigation of HF risk has been published to date. We have investigated the association of 2,478,304 single-nucleotide polymorphisms with incident HF by meta-analyzing data from 4 community-based prospective cohorts: the Atherosclerosis Risk in Communities Study, the Cardiovascular Health Study, the Framingham Heart Study, and the Rotterdam Study. METHODS AND RESULTS: Eligible participants for these analyses were of European or African ancestry and free of clinical HF at baseline. Each study independently conducted genome-wide scans and imputed data to the approximately 2.5 million single-nucleotide polymorphisms in HapMap. Within each study, Cox proportional hazards regression models provided age- and sex-adjusted estimates of the association between each variant and time to incident HF. Fixed-effect meta-analyses combined results for each single-nucleotide polymorphism from the 4 cohorts to produce an overall association estimate and P value. A genome-wide significance P value threshold was set a priori at 5.0x10(-7). During a mean follow-up of 11.5 years, 2526 incident HF events (12%) occurred in 20 926 European-ancestry participants. The meta-analysis identified a genome-wide significant locus at chromosomal position 15q22 (1.4x10(-8)), which was 58.8 kb from USP3. Among 2895 African-ancestry participants, 466 incident HF events (16%) occurred during a mean follow-up of 13.7 years. One genome-wide significant locus was identified at 12q14 (6.7x10(-8)), which was 6.3 kb from LRIG3. CONCLUSIONS: We identified 2 loci that were associated with incident HF and exceeded genome-wide significance. The findings merit replication in other community-based settings of incident HF.
Keywords: African Americans; Aged; Aged, 80 and over; Cohort Studies; Endopeptidases; European Continental Ancestry Group; Female; Genome-Wide Association Study; Heart Failure; Humans; Incidence; Male; Middle Aged; Polymorphism, Single Nucleotide; Risk; Ubiquitin-Specific Proteases

Bayesian methods for meta-analysis of causal relationships estimated using genetic instrumental variables. - Burgess, Stephen; Thompson, Simon G; Burgess, S; Thompson, S G; Andrews, G; Samani, N J; Hall, A; Whincup, P; Morris, R; Lawlor, D A; Davey Smith, G; Timpson, N; et al. (Stat Med, 2010)
Genetic markers can be used as instrumental variables, in an analogous way to randomization in a clinical trial, to estimate the causal relationship between a phenotype and an outcome variable. Our purpose is to extend the existing methods for such Mendelian randomization studies to the context of multiple genetic markers measured in multiple studies, based on the analysis of individual participant data. First, for a single genetic marker in one study, we show that the usual ratio of coefficients approach can be reformulated as a regression with heterogeneous error in the explanatory variable. This can be implemented using a Bayesian approach, which is next extended to include multiple genetic markers. We then propose a hierarchical model for undertaking a meta-analysis of multiple studies, in which it is not necessary that the same genetic markers are measured in each study. This provides an overall estimate of the causal relationship between the phenotype and the outcome, and an assessment of its heterogeneity across studies. As an example, we estimate the causal relationship of blood concentrations of C-reactive protein on fibrinogen levels using data from 11 studies. These methods provide a flexible framework for efficient estimation of causal relationships derived from multiple studies. Issues discussed include weak instrument bias, analysis of binary outcome data such as disease risk, missing genetic data, and the use of haplotypes.
Keywords: Bayes Theorem; Biostatistics; C-Reactive Protein; Fibrinogen; Genetic Markers; Humans; Meta-Analysis as Topic; Models, Statistical; Phenotype; Polymorphism, Single Nucleotide

Biological, clinical and population relevance of 95 loci for blood lipids. - Teslovich, Tanya M; Musunuru, Kiran; Smith, Albert V; Edmondson, Andrew C; Stylianou, Ioannis M; Koseki, Masahiro; Pirruccello, James P; Ripatti, Samuli; Chasman, Daniel I; Willer, Cristen J; Johansen, Christopher T; Fouchier, Sigrid W; et al. (Nature, 2010)
Plasma concentrations of total cholesterol, low-density lipoprotein cholesterol, high-density lipoprotein cholesterol and triglycerides are among the most important risk factors for coronary artery disease (CAD) and are targets for therapeutic intervention. We screened the genome for common variants associated with plasma lipids in >100,000 individuals of European ancestry. Here we report 95 significantly associated loci (P < 5 x 10(-8)), with 59 showing genome-wide significant association with lipid traits for the first time. The newly reported associations include single nucleotide polymorphisms (SNPs) near known lipid regulators (for example, CYP7A1, NPC1L1 and SCARB1) as well as in scores of loci not previously implicated in lipoprotein metabolism. The 95 loci contribute not only to normal variation in lipid traits but also to extreme lipid phenotypes and have an impact on lipid traits in three non-European populations (East Asians, South Asians and African Americans). Our results identify several novel loci associated with plasma lipids that are also associated with CAD. Finally, we validated three of the novel genes-GALNT2, PPP1R3B and TTC39B-with experiments in mouse models. Taken together, our findings provide the foundation to develop a broader biological understanding of lipoprotein metabolism and to identify new therapeutic opportunities for the prevention of CAD.
Keywords: African Americans; Animals; Asian Continental Ancestry Group; Cholesterol, HDL; Cholesterol, LDL; Coronary Artery Disease; Europe; European Continental Ancestry Group; Female; Genetic Loci; Genome-Wide Association Study; Genotype; Humans; Lipid Metabolism; Lipids; Liver; Male; Mice; N-Acetylgalactosaminyltransferases; Phenotype; Polymorphism, Single Nucleotide; Protein Phosphatase 1; Reproducibility of Results; Triglycerides

Cancer linked to Alzheimer disease but not vascular dementia. - Roe, C M; Fitzpatrick, A L; Xiong, C; Sieh, W; Kuller, L; Miller, J P; Williams, M M; Kopan, R; Behrens, M I; Morris, J C (Neurology, 2010)
OBJECTIVE: To investigate whether cancer is associated with Alzheimer disease (AD) and vascular dementia (VaD). METHODS: Cox proportional hazards models were used to test associations between prevalent dementia and risk of future cancer hospitalization, and associations between prevalent cancer and risk of subsequent dementia. Participants in the Cardiovascular Health Study-Cognition Substudy, a prospective cohort study, aged 65 years or older (n = 3,020) were followed a mean of 5.4 years for dementia and 8.3 years for cancer. RESULTS: The presence of any AD (pure AD + mixed AD/VaD; hazard ratio [HR] = 0.41, 95% confidence interval [CI] = 0.20-0.84) and pure AD (HR = 0.31, 95% CI = 0.12-0.86) was associated with a reduced risk of future cancer hospitalization, adjusted for demographic factors, smoking, obesity, and physical activity. No significant associations were found between dementia at baseline and rate of cancer hospitalizations for participants with diagnoses of VaD. Prevalent cancer was associated with reduced risk of any AD (HR = 0.72; 95% CI = 0.52-0.997) and pure AD (HR = 0.57; 95% CI = 0.36-0.90) among white subjects after adjustment for demographics, number of APOE epsilon4 alleles, hypertension, diabetes, and coronary heart disease; the opposite association was found among minorities, but the sample size was too small to provide stable estimates. No significant association was found between cancer and subsequent development of VaD. CONCLUSIONS: In white older adults, prevalent Alzheimer disease (AD) was longitudinally associated with a reduced risk of cancer, and a history of cancer was associated with a reduced risk of AD. Together with other work showing associations between cancer and Parkinson disease, these findings suggest the possibility that cancer is linked to neurodegeneration.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Cohort Studies; Dementia, Vascular; European Continental Ancestry Group; Female; Genetic Predisposition to Disease; Hospitalization; Humans; Male; Neoplasms; Nerve Degeneration; Parkinson Disease; Prevalence; Proportional Hazards Models; Prospective Studies; Risk Assessment; Risk Factors

Candidate gene association resource (CARe): design, methods, and proof of concept. - Musunuru, Kiran; Lettre, Guillaume; Young, Taylor; Farlow, Deborah N; Pirruccello, James P; Ejebe, Kenechi G; Keating, Brendan J; Yang, Qiong; Chen, Ming-Huei; Lapchyk, Nina; Crenshaw, Andrew; Ziaugra, Liuda; et al. (Circ Cardiovasc Genet, 2010)
BACKGROUND: The National Heart, Lung, and Blood Institute's Candidate Gene Association Resource (CARe), a planned cross-cohort analysis of genetic variation in cardiovascular, pulmonary, hematologic, and sleep-related traits, comprises >40,000 participants representing 4 ethnic groups in 9 community-based cohorts. The goals of CARe include the discovery of new variants associated with traits using a candidate gene approach and the discovery of new variants using the genome-wide association mapping approach specifically in African Americans. METHODS AND RESULTS: CARe has assembled DNA samples for >40,000 individuals self-identified as European American, African American, Hispanic, or Chinese American, with accompanying data on hundreds of phenotypes that have been standardized and deposited in the CARe Phenotype Database. All participants were genotyped for 7 single-nucleotide polymorphisms (SNPs) selected based on prior association evidence. We performed association analyses relating each of these SNPs to lipid traits, stratified by sex and ethnicity, and adjusted for age and age squared. In at least 2 of the ethnic groups, SNPs near CETP, LIPC, and LPL strongly replicated for association with high-density lipoprotein cholesterol concentrations, PCSK9 with low-density lipoprotein cholesterol levels, and LPL and APOA5 with serum triglycerides. Notably, some SNPs showed varying effect sizes and significance of association in different ethnic groups. CONCLUSIONS: The CARe Pilot Study validates the operational framework for phenotype collection, SNP genotyping, and analytic pipeline of the CARe project and validates the planned candidate gene study of approximately 2000 biological candidate loci in all participants and genome-wide association study in approximately 8000 African American participants. CARe will serve as a valuable resource for the scientific community.
Keywords: African Americans; Cholesterol, HDL; Cholesterol, LDL; Cohort Studies; Databases, Genetic; European Continental Ancestry Group; Genetic Association Studies; Genotype; Humans; Phenotype; Pilot Projects; Polymorphism, Single Nucleotide; Research Design; Triglycerides

Chronic medical conditions and the sex-based disparity in disability: the Cardiovascular Health Study. - Whitson, Heather E; Landerman, Lawrence R; Newman, Anne B; Fried, Linda P; Pieper, Carl F; Cohen, Harvey Jay (J Gerontol A Biol Sci Med Sci, 2010)
BACKGROUND: Older women experience disability more commonly than their male peers. This disparity may be due, in part, to sex-based differences in the prevalence or the disabling effects of common medical conditions. The objectives of this analysis were to (a) quantify the extent to which excess disability in women is explained by higher prevalence of selected medical conditions and (b) evaluate whether the same conditions have differing effects on disability in men and women. METHODS: We analyzed cross-sectional data from 5,888 community-dwelling older men and women. Disability was defined as difficulty with greater than or equal to one activity of daily living. Thirteen medical conditions were assessed by self-report, testing, or record review. RESULTS: Controlling for age, race, education, and marital status, women were more likely to experience disability (odds ratio = 1.70, 95% confidence interval = 1.36-2.11). Higher prevalence of arthritis and obesity in women explained 30.2% and 12.9%, respectively, of the sex-based difference in disability rates, whereas male prevalent diseases like vascular conditions and emphysema narrowed the disability gap. Women with arthritis, hearing problems, coronary artery disease, congestive heart failure, stroke, and claudication were more likely to exhibit disability compared with men with the same conditions (p < .001). CONCLUSIONS: Efforts to lessen sex-based inequality in disability should focus on reducing the prevalence of arthritis and obesity. Future generations may see greater functional disparity if rates of vascular disease and emphysema rise among women. Several conditions were more often associated with disability in women, suggesting additional sex-based differences in the disablement process.
Keywords: Aged; Arthritis; Cardiovascular Diseases; Chronic Disease; Cohort Studies; Comorbidity; Cross-Sectional Studies; Disabled Persons; Emphysema; Female; Hearing Disorders; Humans; Male; Obesity; Prevalence; Sex Distribution

Cognition and the risk of hospitalization for serious falls in the elderly: results from the Cardiovascular Health Study. - Welmerink, Diana B; Longstreth, W T; Lyles, Mary F; Fitzpatrick, Annette L (J Gerontol A Biol Sci Med Sci, 2010)
BACKGROUND: Many elderly adults fall every year, sometimes resulting in serious injury and hospitalization. Although impaired cognition is a risk factor for injurious falls, little is known about cognitive decline above the threshold of impairment and risk of serious falls in community-dwelling seniors. METHODS: In total, 702 of 5,356 older adults participating in the Cardiovascular Health Study experienced an injurious fall between 1990 and 2005, as indicated by hospitalization records. General cognition was measured annually with the Modified Mini-Mental State Examination and processing speed with the Digit Symbol Substitution Test. The Cox regression model was used to calculate hazard ratio and 95% confidence interval with and without time-dependent covariates and adjusted for known risk factors. RESULTS: Participants with slightly decreased Digit Symbol Substitution Test scores were at increased risk for a serious fall (hazard ratio = 1.58, 95% confidence interval = 1.15-2.17). The risk continued to increase with each quartile decrease in Digit Symbol Substitution Test score. Participants without prevalent cardiovascular disease at baseline and decreased Modified Mini-Mental State Examination scores (80-89) had a 45% increased risk for a serious fall and those at high risk for dementia (<80) were at twice the risk as participants scoring above 90 (hazard ratio = 2.16, 95% confidence interval = 1.60-2.91). CONCLUSIONS: Both decreased general cognition and decreased processing speed appear to be potential risk factors for serious falls in the elderly. When assessing the risk of serious falls in elderly patients, clinicians should consider usual factors like gait instability and sensory impairment as well as less obvious ones such as cardiovascular disease and cognitive function in nondemented adults.
Keywords: Accidental Falls; Aged; Aged, 80 and over; Chi-Square Distribution; Cognition Disorders; Female; Follow-Up Studies; Geriatric Assessment; Hospitalization; Humans; Male; Mental Status Schedule; Physical Examination; Proportional Hazards Models; Risk Assessment; Risk Factors; Surveys and Questionnaires

Combined association of lipids and blood pressure in relation to incident cardiovascular disease in the elderly: the cardiovascular health study. - Wong, Nathan D; Lopez, Victor A; Roberts, Craig S; Solomon, Henry A; Burke, Gregory L; Kuller, Lewis; Tracy, Russell; Yanez, David; Psaty, Bruce M (Am J Hypertens, 2010)
BACKGROUND: Hypertension and dyslipidemia are highly prevalent in the elderly. We studied the combined impact of both conditions on cardiovascular disease (CVD) events. METHODS: We studied 4,311 participants aged 65-98 (61.2% female) from the Cardiovascular Health Study (CHS), a longitudinal epidemiologic study, with no prior CVD. We evaluated the relation of low-density lipoprotein (LDL), high-density lipoprotein (HDL), or non-HDL-cholesterol combined with blood pressure (BP) categories to incident CVD-including coronary heart disease (CHD) (angina, myocardial infarction (MI), angioplasty, coronary bypass surgery, or CHD death), stroke, claudication, and CVD death over 15 years. RESULTS: CVD incidence (per 1,000 person years) ranged from 38.4 when BP <120/80 mm Hg and LDL-C <100 mg/dl to 94.8 when BP >or=160/100 mm Hg and LDL-C >or=160 mg/dl, and from 28.9 when BP <120/80 mm Hg and HDL >60 mg/dl to 87.1 for a BP >or=160/100 and HDL-C <40 mg/dl. Compared with those with BP <120/80 mm Hg with either LDL-C <100 mg/dl or HDL-C >60 mg/dl, hazard ratios (HRs) for CVD events were 2.1 when BP >or=160/100 mm Hg and LDL-C >or=160 mg/dl and 2.1 when BP >or=160/100 and HDL-C <40 mg/dl (all P < 0.01), with similar results for non-HDL-C. Elevated BP was associated with increased risk across all lipid levels. Increased LDL-C added risk mainly when BP <140/90 mm Hg, but lower HDL-C also predicted CVD in those with higher BP. CONCLUSION: Increased BP confers increased risks for CVD in elderly persons across all lipid levels. Although increased LDL-C added risk mainly when BP <140/90 mm Hg, low HDL-C added risk also in those with hypertension. These results document the importance of combined hypertension and dyslipidemia.
Keywords: Age Factors; Aged; Aged, 80 and over; Blood Pressure; Cardiovascular Diseases; Cholesterol, HDL; Cholesterol, LDL; Diabetes Mellitus; Female; Health Surveys; Humans; Likelihood Functions; Lipids; Male; Proportional Hazards Models; Sex Factors; Smoking; Socioeconomic Factors; United States

Commentary on "Developing a national strategy to prevent dementia: Leon Thal Symposium 2009." Dementia risk indices: A framework for identifying individuals with a high dementia risk. - Barnes, Deborah E; Covinsky, Kenneth E; Whitmer, Rachel A; Kuller, Lewis H; Lopez, Oscar L; Yaffe, Kristine (Alzheimers Dement, 2010)
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Dementia; Diagnosis, Differential; Disability Evaluation; Early Diagnosis; Humans; National Health Programs; Predictive Value of Tests; Prognosis; Risk Assessment; Risk Factors; United States

Common genetic determinants of vitamin D insufficiency: a genome-wide association study. - Wang, Thomas J; Zhang, Feng; Richards, J Brent; Kestenbaum, Bryan; van Meurs, Joyce B; Berry, Diane; Kiel, Douglas P; Streeten, Elizabeth A; Ohlsson, Claes; Koller, Daniel L; Peltonen, Leena; Cooper, Jason D; et al. (Lancet, 2010)
BACKGROUND: Vitamin D is crucial for maintenance of musculoskeletal health, and might also have a role in extraskeletal tissues. Determinants of circulating 25-hydroxyvitamin D concentrations include sun exposure and diet, but high heritability suggests that genetic factors could also play a part. We aimed to identify common genetic variants affecting vitamin D concentrations and risk of insufficiency. METHODS: We undertook a genome-wide association study of 25-hydroxyvitamin D concentrations in 33 996 individuals of European descent from 15 cohorts. Five epidemiological cohorts were designated as discovery cohorts (n=16 125), five as in-silico replication cohorts (n=9367), and five as de-novo replication cohorts (n=8504). 25-hydroxyvitamin D concentrations were measured by radioimmunoassay, chemiluminescent assay, ELISA, or mass spectrometry. Vitamin D insufficiency was defined as concentrations lower than 75 nmol/L or 50 nmol/L. We combined results of genome-wide analyses across cohorts using Z-score-weighted meta-analysis. Genotype scores were constructed for confirmed variants. FINDINGS: Variants at three loci reached genome-wide significance in discovery cohorts for association with 25-hydroxyvitamin D concentrations, and were confirmed in replication cohorts: 4p12 (overall p=1.9x10(-109) for rs2282679, in GC); 11q12 (p=2.1x10(-27) for rs12785878, near DHCR7); and 11p15 (p=3.3x10(-20) for rs10741657, near CYP2R1). Variants at an additional locus (20q13, CYP24A1) were genome-wide significant in the pooled sample (p=6.0x10(-10) for rs6013897). Participants with a genotype score (combining the three confirmed variants) in the highest quartile were at increased risk of having 25-hydroxyvitamin D concentrations lower than 75 nmol/L (OR 2.47, 95% CI 2.20-2.78, p=2.3x10(-48)) or lower than 50 nmol/L (1.92, 1.70-2.16, p=1.0x10(-26)) compared with those in the lowest quartile. INTERPRETATION: Variants near genes involved in cholesterol synthesis, hydroxylation, and vitamin D transport affect vitamin D status. Genetic variation at these loci identifies individuals who have substantially raised risk of vitamin D insufficiency. FUNDING: Full funding sources listed at end of paper (see Acknowledgments).
Keywords: Canada; Chromosomes, Human, Pair 11; Chromosomes, Human, Pair 4; Cohort Studies; Dietary Supplements; Europe; European Continental Ancestry Group; Genetic Predisposition to Disease; Genome-Wide Association Study; Heterozygote; Homozygote; Humans; Immunoassay; International Cooperation; Linkage Disequilibrium; Polymorphism, Single Nucleotide; Seasons; United States; Vitamin D; Vitamin D Deficiency

Common genetic variants associate with serum phosphorus concentration. - Kestenbaum, Bryan; Glazer, Nicole L; Köttgen, Anna; Felix, Janine F; Hwang, Shih-Jen; Liu, Yongmei; Lohman, Kurt; Kritchevsky, Stephen B; Hausman, Dorothy B; Petersen, Ann-Kristin; Gieger, Christian; Ried, Janina S; et al. (J Am Soc Nephrol, 2010)
Phosphorus is an essential mineral that maintains cellular energy and mineralizes the skeleton. Because complex actions of ion transporters and regulatory hormones regulate serum phosphorus concentrations, genetic variation may determine interindividual variation in phosphorus metabolism. Here, we report a comprehensive genome-wide association study of serum phosphorus concentration. We evaluated 16,264 participants of European ancestry from the Cardiovascular Heath Study, Atherosclerosis Risk in Communities Study, Framingham Offspring Study, and the Rotterdam Study. We excluded participants with an estimated GFR <45 ml/min per 1.73 m(2) to focus on phosphorus metabolism under normal conditions. We imputed genotypes to approximately 2.5 million single-nucleotide polymorphisms in the HapMap and combined study-specific findings using meta-analysis. We tested top polymorphisms from discovery cohorts in a 5444-person replication sample. Polymorphisms in seven loci with minor allele frequencies 0.08 to 0.49 associate with serum phosphorus concentration (P = 3.5 x 10(-16) to 3.6 x 10(-7)). Three loci were near genes encoding the kidney-specific type IIa sodium phosphate co-transporter (SLC34A1), the calcium-sensing receptor (CASR), and fibroblast growth factor 23 (FGF23), proteins that contribute to phosphorus metabolism. We also identified genes encoding phosphatases, kinases, and phosphodiesterases that have yet-undetermined roles in phosphorus homeostasis. In the replication sample, five of seven top polymorphisms associate with serum phosphorous concentrations (P < 0.05 for each). In conclusion, common genetic variants associate with serum phosphorus in the general population. Further study of the loci identified in this study may help elucidate mechanisms of phosphorus regulation.
Keywords: Adult; Aged; European Continental Ancestry Group; Female; Fibroblast Growth Factors; Gene Frequency; Genetic Loci; Genetic Variation; Genome-Wide Association Study; Humans; Kidney; Male; Middle Aged; Phosphorus; Polymorphism, Single Nucleotide; Receptors, Calcium-Sensing; Sex Factors; Sodium-Phosphate Cotransporter Proteins, Type IIa

Common variants in 22 loci are associated with QRS duration and cardiac ventricular conduction. - Sotoodehnia, Nona; Isaacs, Aaron; de Bakker, Paul I W; Dörr, Marcus; Newton-Cheh, Christopher; Nolte, Ilja M; van der Harst, Pim; Müller, Martina; Eijgelsheim, Mark; Alonso, Alvaro; Hicks, Andrew A; Padmanabhan, Sandosh; et al. (Nat Genet, 2010)
The QRS interval, from the beginning of the Q wave to the end of the S wave on an electrocardiogram, reflects ventricular depolarization and conduction time and is a risk factor for mortality, sudden death and heart failure. We performed a genome-wide association meta-analysis in 40,407 individuals of European descent from 14 studies, with further genotyping in 7,170 additional Europeans, and we identified 22 loci associated with QRS duration (P < 5 × 10(-8)). These loci map in or near genes in pathways with established roles in ventricular conduction such as sodium channels, transcription factors and calcium-handling proteins, but also point to previously unidentified biologic processes, such as kinase inhibitors and genes related to tumorigenesis. We demonstrate that SCN10A, a candidate gene at the most significantly associated locus in this study, is expressed in the mouse ventricular conduction system, and treatment with a selective SCN10A blocker prolongs QRS duration. These findings extend our current knowledge of ventricular depolarization and conduction.
Keywords: Animals; Animals, Newborn; Chromosomes, Human; Computational Biology; Electrocardiography; Genetic Loci; Genome-Wide Association Study; Heart Conduction System; Humans; Mice; Mice, Transgenic; Models, Animal; Myocytes, Cardiac; NAV1.8 Voltage-Gated Sodium Channel; Polymorphism, Single Nucleotide; Sodium Channels

Common variants in KCNN3 are associated with lone atrial fibrillation. - Ellinor, Patrick T; Lunetta, Kathryn L; Glazer, Nicole L; Pfeufer, Arne; Alonso, Alvaro; Chung, Mina K; Sinner, Moritz F; de Bakker, Paul I W; Mueller, Martina; Lubitz, Steven A; Fox, Ervin; Darbar, Dawood; et al. (Nat Genet, 2010)
Atrial fibrillation (AF) is the most common sustained arrhythmia. Previous studies have identified several genetic loci associated with typical AF. We sought to identify common genetic variants underlying lone AF. This condition affects a subset of individuals without overt heart disease and with an increased heritability of AF. We report a meta-analysis of genome-wide association studies conducted using 1,335 individuals with lone AF (cases) and 12,844 unaffected individuals (referents). Cases were obtained from the German AF Network, Heart and Vascular Health Study, the Atherosclerosis Risk in Communities Study, the Cleveland Clinic and Massachusetts General Hospital. We identified an association on chromosome 1q21 to lone AF (rs13376333, adjusted odds ratio = 1.56; P = 6.3 x 10(-12)), and we replicated this association in two independent cohorts with lone AF (overall combined odds ratio = 1.52, 95% CI 1.40-1.64; P = 1.83 x 10(-21)). rs13376333 is intronic to KCNN3, which encodes a potassium channel protein involved in atrial repolarization.
Keywords: Adolescent; Adult; Aged; Atrial Fibrillation; Case-Control Studies; Cohort Studies; Female; Genome-Wide Association Study; Humans; Introns; Male; Meta-Analysis as Topic; Middle Aged; Polymorphism, Single Nucleotide; Small-Conductance Calcium-Activated Potassium Channels; Young Adult

Common variants in the calcium-sensing receptor gene are associated with total serum calcium levels. - O'Seaghdha, Conall M; Yang, Qiong; Glazer, Nicole L; Leak, Tennille S; Dehghan, Abbas; Smith, Albert V; Kao, W H Linda; Lohman, Kurt; Hwang, Shih-Jen; Johnson, Andrew D; Hofman, Albert; Uitterlinden, André G; et al. (Hum Mol Genet, 2010)
Serum calcium levels are tightly regulated. We performed genome-wide association studies (GWAS) in population-based studies participating in the CHARGE Consortium to uncover common genetic variations associated with total serum calcium levels. GWAS of serum calcium concentrations was performed in 20 611 individuals of European ancestry for ∼2.5 million genotyped and imputed single-nucleotide polymorphisms (SNPs). The SNP with the lowest P-value was rs17251221 (P = 2.4 * 10(-22), minor allele frequency 14%) in the calcium-sensing receptor gene (CASR). This lead SNP was associated with higher serum calcium levels [0.06 mg/dl (0.015 mmol/l) per copy of the minor G allele] and accounted for 0.54% of the variance in serum calcium concentrations. The identification of variation in CASR that influences serum calcium concentration confirms the results of earlier candidate gene studies. The G allele of rs17251221 was also associated with higher serum magnesium levels (P = 1.2 * 10(-3)), lower serum phosphate levels (P = 2.8 * 10(-7)) and lower bone mineral density at the lumbar spine (P = 0.038), but not the femoral neck. No additional genomic loci contained SNPs associated at genome-wide significance (P < 5 * 10(-8)). These associations resemble clinical characteristics of patients with familial hypocalciuric hypercalcemia, an autosomal-dominant disease arising from rare inactivating mutations in the CASR gene. We conclude that common genetic variation in the CASR gene is associated with similar but milder features in the general population.
Keywords: Adult; Calcium; Female; Humans; Male; Middle Aged; Polymorphism, Single Nucleotide; Receptors, Calcium-Sensing

Diabetes mellitus, fasting blood glucose concentration, and risk of vascular disease: a collaborative meta-analysis of 102 prospective studies. - Sarwar, N; Gao, P; Seshasai, S R Kondapally; Gobin, R; Kaptoge, S; Di Angelantonio, E; Ingelsson, E; Lawlor, D A; Selvin, E; Stampfer, M; Stehouwer, C D A; Lewington, S; et al. (Lancet, 2010)
BACKGROUND: Uncertainties persist about the magnitude of associations of diabetes mellitus and fasting glucose concentration with risk of coronary heart disease and major stroke subtypes. We aimed to quantify these associations for a wide range of circumstances. METHODS: We undertook a meta-analysis of individual records of diabetes, fasting blood glucose concentration, and other risk factors in people without initial vascular disease from studies in the Emerging Risk Factors Collaboration. We combined within-study regressions that were adjusted for age, sex, smoking, systolic blood pressure, and body-mass index to calculate hazard ratios (HRs) for vascular disease. FINDINGS: Analyses included data for 698 782 people (52 765 non-fatal or fatal vascular outcomes; 8.49 million person-years at risk) from 102 prospective studies. Adjusted HRs with diabetes were: 2.00 (95% CI 1.83-2.19) for coronary heart disease; 2.27 (1.95-2.65) for ischaemic stroke; 1.56 (1.19-2.05) for haemorrhagic stroke; 1.84 (1.59-2.13) for unclassified stroke; and 1.73 (1.51-1.98) for the aggregate of other vascular deaths. HRs did not change appreciably after further adjustment for lipid, inflammatory, or renal markers. HRs for coronary heart disease were higher in women than in men, at 40-59 years than at 70 years and older, and with fatal than with non-fatal disease. At an adult population-wide prevalence of 10%, diabetes was estimated to account for 11% (10-12%) of vascular deaths. Fasting blood glucose concentration was non-linearly related to vascular risk, with no significant associations between 3.90 mmol/L and 5.59 mmol/L. Compared with fasting blood glucose concentrations of 3.90-5.59 mmol/L, HRs for coronary heart disease were: 1.07 (0.97-1.18) for lower than 3.90 mmol/L; 1.11 (1.04-1.18) for 5.60-6.09 mmol/L; and 1.17 (1.08-1.26) for 6.10-6.99 mmol/L. In people without a history of diabetes, information about fasting blood glucose concentration or impaired fasting glucose status did not significantly improve metrics of vascular disease prediction when added to information about several conventional risk factors. INTERPRETATION: Diabetes confers about a two-fold excess risk for a wide range of vascular diseases, independently from other conventional risk factors. In people without diabetes, fasting blood glucose concentration is modestly and non-linearly associated with risk of vascular disease. FUNDING: British Heart Foundation, UK Medical Research Council, and Pfizer.
Keywords: Adult; Aged; Blood Glucose; Coronary Disease; Diabetes Complications; Diabetes Mellitus; Fasting; Female; Humans; Male; Middle Aged; Risk Factors; Stroke

Differential white blood cell count and type 2 diabetes: systematic review and meta-analysis of cross-sectional and prospective studies. - Gkrania-Klotsas, Effrossyni; Ye, Zheng; Cooper, Andrew J; Sharp, Stephen J; Luben, Robert; Biggs, Mary L; Chen, Liang-Kung; Gokulakrishnan, Kuppan; Hanefeld, Markolf; Ingelsson, Erik; Lai, Wen-An; Lin, Shih-Yi; et al. (PLoS One, 2010)
OBJECTIVE: Biological evidence suggests that inflammation might induce type 2 diabetes (T2D), and epidemiological studies have shown an association between higher white blood cell count (WBC) and T2D. However, the association has not been systematically investigated. RESEARCH DESIGN AND METHODS: Studies were identified through computer-based and manual searches. Previously unreported studies were sought through correspondence. 20 studies were identified (8,647 T2D cases and 85,040 non-cases). Estimates of the association of WBC with T2D were combined using random effects meta-analysis; sources of heterogeneity as well as presence of publication bias were explored. RESULTS: The combined relative risk (RR) comparing the top to bottom tertile of the WBC count was 1.61 (95% CI: 1.45; 1.79, p = 1.5*10(-18)). Substantial heterogeneity was present (I(2) = 83%). For granulocytes the RR was 1.38 (95% CI: 1.17; 1.64, p = 1.5*10(-4)), for lymphocytes 1.26 (95% CI: 1.02; 1.56, p = 0.029), and for monocytes 0.93 (95% CI: 0.68; 1.28, p = 0.67) comparing top to bottom tertile. In cross-sectional studies, RR was 1.74 (95% CI: 1.49; 2.02, p = 7.7*10(-13)), while in cohort studies it was 1.48 (95% CI: 1.22; 1.79, p = 7.7*10(-5)). We assessed the impact of confounding in EPIC-Norfolk study and found that the age and sex adjusted HR of 2.19 (95% CI: 1.74; 2.75) was attenuated to 1.82 (95% CI: 1.45; 2.29) after further accounting for smoking, T2D family history, physical activity, education, BMI and waist circumference. CONCLUSIONS: A raised WBC is associated with higher risk of T2D. The presence of publication bias and failure to control for all potential confounders in all studies means the observed association is likely an overestimate.
Keywords: Adult; Aged; Cross-Sectional Studies; Diabetes Mellitus, Type 2; Female; Humans; Leukocyte Count; Male; Middle Aged; Prospective Studies

Four novel Loci (19q13, 6q24, 12q24, and 5q14) influence the microcirculation in vivo. - Ikram, M Kamran; Sim, Xueling; Xueling, Sim; Jensen, Richard A; Cotch, Mary Frances; Hewitt, Alex W; Ikram, M Arfan; Wang, Jie Jin; Klein, Ronald; Klein, Barbara E K; Breteler, Monique M B; Cheung, Ning; et al. (PLoS Genet, 2010)
There is increasing evidence that the microcirculation plays an important role in the pathogenesis of cardiovascular diseases. Changes in retinal vascular caliber reflect early microvascular disease and predict incident cardiovascular events. We performed a genome-wide association study to identify genetic variants associated with retinal vascular caliber. We analyzed data from four population-based discovery cohorts with 15,358 unrelated Caucasian individuals, who are members of the Cohort for Heart and Aging Research in Genomic Epidemiology (CHARGE) consortium, and replicated findings in four independent Caucasian cohorts (n  =  6,652). All participants had retinal photography and retinal arteriolar and venular caliber measured from computer software. In the discovery cohorts, 179 single nucleotide polymorphisms (SNP) spread across five loci were significantly associated (p<5.0×10(-8)) with retinal venular caliber, but none showed association with arteriolar caliber. Collectively, these five loci explain 1.0%-3.2% of the variation in retinal venular caliber. Four out of these five loci were confirmed in independent replication samples. In the combined analyses, the top SNPs at each locus were: rs2287921 (19q13; p  =  1.61×10(-25), within the RASIP1 locus), rs225717 (6q24; p = 1.25×10(-16), adjacent to the VTA1 and NMBR loci), rs10774625 (12q24; p  =  2.15×10(-13), in the region of ATXN2,SH2B3 and PTPN11 loci), and rs17421627 (5q14; p = 7.32×10(-16), adjacent to the MEF2C locus). In two independent samples, locus 12q24 was also associated with coronary heart disease and hypertension. Our population-based genome-wide association study demonstrates four novel loci associated with retinal venular caliber, an endophenotype of the microcirculation associated with clinical cardiovascular disease. These data provide further insights into the contribution and biological mechanisms of microcirculatory changes that underlie cardiovascular disease.
Keywords: Adolescent; Adult; Aged; Aged, 80 and over; Cardiovascular Diseases; Child; Child, Preschool; Chromosomes, Human, Pair 12; Chromosomes, Human, Pair 19; Chromosomes, Human, Pair 5; Chromosomes, Human, Pair 6; Cohort Studies; European Continental Ancestry Group; Female; Genetic Loci; Genome-Wide Association Study; Humans; Male; Meta-Analysis as Topic; Microcirculation; Middle Aged; Polymorphism, Single Nucleotide; Retinal Vessels; Young Adult

Genetic ancestry in lung-function predictions. - Kumar, Rajesh; Seibold, Max A; Aldrich, Melinda C; Williams, L Keoki; Reiner, Alex P; Colangelo, Laura; Galanter, Joshua; Gignoux, Christopher; Hu, Donglei; Sen, Saunak; Choudhry, Shweta; Peterson, Edward L; et al. (N Engl J Med, 2010)
BACKGROUND: Self-identified race or ethnic group is used to determine normal reference standards in the prediction of pulmonary function. We conducted a study to determine whether the genetically determined percentage of African ancestry is associated with lung function and whether its use could improve predictions of lung function among persons who identified themselves as African American. METHODS: We assessed the ancestry of 777 participants self-identified as African American in the Coronary Artery Risk Development in Young Adults (CARDIA) study and evaluated the relation between pulmonary function and ancestry by means of linear regression. We performed similar analyses of data for two independent cohorts of subjects identifying themselves as African American: 813 participants in the Health, Aging, and Body Composition (HABC) study and 579 participants in the Cardiovascular Health Study (CHS). We compared the fit of two types of models to lung-function measurements: models based on the covariates used in standard prediction equations and models incorporating ancestry. We also evaluated the effect of the ancestry-based models on the classification of disease severity in two asthma-study populations. RESULTS: African ancestry was inversely related to forced expiratory volume in 1 second (FEV(1)) and forced vital capacity in the CARDIA cohort. These relations were also seen in the HABC and CHS cohorts. In predicting lung function, the ancestry-based model fit the data better than standard models. Ancestry-based models resulted in the reclassification of asthma severity (based on the percentage of the predicted FEV(1)) in 4 to 5% of participants. CONCLUSIONS: Current predictive equations, which rely on self-identified race alone, may misestimate lung function among subjects who identify themselves as African American. Incorporating ancestry into normative equations may improve lung-function estimates and more accurately categorize disease severity. (Funded by the National Institutes of Health and others.)
Keywords: Adolescent; Adult; African Americans; Aged; Aged, 80 and over; Female; Forced Expiratory Volume; Genetic Markers; Genotype; Humans; Linear Models; Male; Middle Aged; Oligonucleotide Array Sequence Analysis; Reference Values; Respiratory Function Tests; Vital Capacity; Young Adult

Genome-wide analysis of genetic loci associated with Alzheimer disease. - Seshadri, Sudha; Fitzpatrick, Annette L; Ikram, M Arfan; DeStefano, Anita L; Gudnason, Vilmundur; Boada, Merce; Bis, Joshua C; Smith, Albert V; Carassquillo, Minerva M; Lambert, Jean Charles; Harold, Denise; Schrijvers, Elisabeth M C; et al. (JAMA, 2010)
CONTEXT: Genome-wide association studies (GWAS) have recently identified CLU, PICALM, and CR1 as novel genes for late-onset Alzheimer disease (AD). OBJECTIVES: To identify and strengthen additional loci associated with AD and confirm these in an independent sample and to examine the contribution of recently identified genes to AD risk prediction in a 3-stage analysis of new and previously published GWAS on more than 35,000 persons (8371 AD cases). DESIGN, SETTING, AND PARTICIPANTS: In stage 1, we identified strong genetic associations (P < 10(-3)) in a sample of 3006 AD cases and 14,642 controls by combining new data from the population-based Cohorts for Heart and Aging Research in Genomic Epidemiology consortium (1367 AD cases [973 incident]) with previously reported results from the Translational Genomics Research Institute and the Mayo AD GWAS. We identified 2708 single-nucleotide polymorphisms (SNPs) with P < 10(-3). In stage 2, we pooled results for these SNPs with the European AD Initiative (2032 cases and 5328 controls) to identify 38 SNPs (10 loci) with P < 10(-5). In stage 3, we combined data for these 10 loci with data from the Genetic and Environmental Risk in AD consortium (3333 cases and 6995 controls) to identify 4 SNPs with P < 1.7x10(-8). These 4 SNPs were replicated in an independent Spanish sample (1140 AD cases and 1209 controls). Genome-wide association analyses were completed in 2007-2008 and the meta-analyses and replication in 2009. MAIN OUTCOME MEASURE: Presence of Alzheimer disease. RESULTS: Two loci were identified to have genome-wide significance for the first time: rs744373 near BIN1 (odds ratio [OR],1.13; 95% confidence interval [CI],1.06-1.21 per copy of the minor allele; P = 1.59x10(-11)) and rs597668 near EXOC3L2/BLOC1S3/MARK4 (OR, 1.18; 95% CI, 1.07-1.29; P = 6.45x10(-9)). Associations of these 2 loci plus the previously identified loci CLU and PICALM with AD were confirmed in the Spanish sample (P < .05). However, although CLU and PICALM were confirmed to be associated with AD in this independent sample, they did not improve the ability of a model that included age, sex, and APOE to predict incident AD (improvement in area under the receiver operating characteristic curve from 0.847 to 0.849 in the Rotterdam Study and 0.702 to 0.705 in the Cardiovascular Health Study). CONCLUSIONS: Two genetic loci for AD were found for the first time to reach genome-wide statistical significance. These findings were replicated in an independent population. Two recently reported associations were also confirmed. These loci did not improve AD risk prediction. While not clinically useful, they may implicate biological pathways useful for future research.
Keywords: Age of Onset; Aged; Alzheimer Disease; Case-Control Studies; Genetic Loci; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Odds Ratio; Polymorphism, Single Nucleotide

Genome-wide association analysis identifies multiple loci related to resting heart rate. - Eijgelsheim, Mark; Newton-Cheh, Christopher; Sotoodehnia, Nona; de Bakker, Paul I W; Müller, Martina; Morrison, Alanna C; Smith, Albert V; Isaacs, Aaron; Sanna, Serena; Dörr, Marcus; Navarro, Pau; Fuchsberger, Christian; et al. (Hum Mol Genet, 2010)
Higher resting heart rate is associated with increased cardiovascular disease and mortality risk. Though heritable factors play a substantial role in population variation, little is known about specific genetic determinants. This knowledge can impact clinical care by identifying novel factors that influence pathologic heart rate states, modulate heart rate through cardiac structure and function or by improving our understanding of the physiology of heart rate regulation. To identify common genetic variants associated with heart rate, we performed a meta-analysis of 15 genome-wide association studies (GWAS), including 38,991 subjects of European ancestry, estimating the association between age-, sex- and body mass-adjusted RR interval (inverse heart rate) and approximately 2.5 million markers. Results with P < 5 × 10(-8) were considered genome-wide significant. We constructed regression models with multiple markers to assess whether results at less stringent thresholds were likely to be truly associated with RR interval. We identified six novel associations with resting heart rate at six loci: 6q22 near GJA1; 14q12 near MYH7; 12p12 near SOX5, c12orf67, BCAT1, LRMP and CASC1; 6q22 near SLC35F1, PLN and c6orf204; 7q22 near SLC12A9 and UfSp1; and 11q12 near FADS1. Associations at 6q22 400 kb away from GJA1, at 14q12 MYH6 and at 1q32 near CD34 identified in previously published GWAS were confirmed. In aggregate, these variants explain approximately 0.7% of RR interval variance. A multivariant regression model including 20 variants with P < 10(-5) increased the explained variance to 1.6%, suggesting that some loci falling short of genome-wide significance are likely truly associated. Future research is warranted to elucidate underlying mechanisms that may impact clinical care.
Keywords: Adult; Aged; Base Pairing; Cohort Studies; Female; Genetic Loci; Genome, Human; Genome-Wide Association Study; Heart Rate; Humans; Male; Middle Aged; Polymorphism, Single Nucleotide; Rest

Genome-wide association identifies multiple ulcerative colitis susceptibility loci. - McGovern, Dermot P B; Gardet, Agnès; Törkvist, Leif; Goyette, Philippe; Essers, Jonah; Taylor, Kent D; Neale, Benjamin M; Ong, Rick T H; Lagacé, Caroline; Li, Chun; Green, Todd; Stevens, Christine R; et al. (Nat Genet, 2010)
Ulcerative colitis is a chronic, relapsing inflammatory condition of the gastrointestinal tract with a complex genetic and environmental etiology. In an effort to identify genetic variation underlying ulcerative colitis risk, we present two distinct genome-wide association studies of ulcerative colitis and their joint analysis with a previously published scan, comprising, in aggregate, 2,693 individuals with ulcerative colitis and 6,791 control subjects. Fifty-nine SNPs from 14 independent loci attained an association significance of P < 10(-5). Seven of these loci exceeded genome-wide significance (P < 5 x 10(-8)). After testing an independent cohort of 2,009 cases of ulcerative colitis and 1,580 controls, we identified 13 loci that were significantly associated with ulcerative colitis (P < 5 x 10(-8)), including the immunoglobulin receptor gene FCGR2A, 5p15, 2p16 and ORMDL3 (orosomucoid1-like 3). We confirmed association with 14 previously identified ulcerative colitis susceptibility loci, and an analysis of acknowledged Crohn's disease loci showed that roughly half of the known Crohn's disease associations are shared with ulcerative colitis. These data implicate approximately 30 loci in ulcerative colitis, thereby providing insight into disease pathogenesis.
Keywords: Colitis, Ulcerative; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Membrane Proteins; Meta-Analysis as Topic; Polymorphism, Single Nucleotide; Receptors, IgG

Genome-wide association studies of MRI-defined brain infarcts: meta-analysis from the CHARGE Consortium. - Debette, Stephanie; Bis, Joshua C; Fornage, Myriam; Schmidt, Helena; Ikram, M Arfan; Sigurdsson, Sigurdur; Heiss, Gerardo; Struchalin, Maksim; Smith, Albert V; van der Lugt, Aad; DeCarli, Charles; Lumley, Thomas; et al. (Stroke, 2010)
BACKGROUND AND PURPOSE: Previous studies examining genetic associations with MRI-defined brain infarct have yielded inconsistent findings. We investigated genetic variation underlying covert MRI infarct in persons without histories of transient ischemic attack or stroke. We performed meta-analysis of genome-wide association studies of white participants in 6 studies comprising the Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) consortium. METHODS: Using 2.2 million genotyped and imputed single nucleotide polymorphisms, each study performed cross-sectional genome-wide association analysis of MRI infarct using age- and sex-adjusted logistic regression models. Study-specific findings were combined in an inverse-variance-weighted meta-analysis, including 9401 participants with mean age 69.7 (19.4% of whom had >or=1 MRI infarct). RESULTS: The most significant association was found with rs2208454 (minor allele frequency, 20%), located in intron 3 of MACRO domain containing 2 gene and in the downstream region of fibronectin leucine-rich transmembrane protein 3 gene. Each copy of the minor allele was associated with lower risk of MRI infarcts (odds ratio, 0.76; 95% confidence interval, 0.68-0.84; P=4.64x10(-7)). Highly suggestive associations (P<1.0x10(-5)) were also found for 22 other single nucleotide polymorphisms in linkage disequilibrium (r(2)>0.64) with rs2208454. The association with rs2208454 did not replicate in independent samples of 1822 white and 644 black participants, although 4 single nucleotide polymorphisms within 200 kb from rs2208454 were associated with MRI infarcts in the black population sample. CONCLUSIONS: This first community-based, genome-wide association study on covert MRI infarcts uncovered novel associations. Although replication of the association with top single nucleotide polymorphisms failed, possibly because of insufficient power, results in the black population sample are encouraging, and further efforts at replication are needed.
Keywords: African Americans; Aged; Brain; Brain Infarction; Cohort Studies; DNA Mutational Analysis; Female; Gene Frequency; Genetic Markers; Genetic Predisposition to Disease; Genetic Testing; Genetic Variation; Genome-Wide Association Study; Humans; Linkage Disequilibrium; Magnetic Resonance Imaging; Male; Middle Aged; Polymorphism, Single Nucleotide; Prospective Studies

Genome-wide association studies of serum magnesium, potassium, and sodium concentrations identify six Loci influencing serum magnesium levels. - Meyer, Tamra E; Verwoert, Germaine C; Hwang, Shih-Jen; Glazer, Nicole L; Smith, Albert V; van Rooij, Frank J A; Ehret, Georg B; Boerwinkle, Eric; Felix, Janine F; Leak, Tennille S; Harris, Tamara B; Yang, Qiong; et al. (PLoS Genet, 2010)
Magnesium, potassium, and sodium, cations commonly measured in serum, are involved in many physiological processes including energy metabolism, nerve and muscle function, signal transduction, and fluid and blood pressure regulation. To evaluate the contribution of common genetic variation to normal physiologic variation in serum concentrations of these cations, we conducted genome-wide association studies of serum magnesium, potassium, and sodium concentrations using approximately 2.5 million genotyped and imputed common single nucleotide polymorphisms (SNPs) in 15,366 participants of European descent from the international CHARGE Consortium. Study-specific results were combined using fixed-effects inverse-variance weighted meta-analysis. SNPs demonstrating genome-wide significant (p<5 x 10(-8)) or suggestive associations (p<4 x 10(-7)) were evaluated for replication in an additional 8,463 subjects of European descent. The association of common variants at six genomic regions (in or near MUC1, ATP2B1, DCDC5, TRPM6, SHROOM3, and MDS1) with serum magnesium levels was genome-wide significant when meta-analyzed with the replication dataset. All initially significant SNPs from the CHARGE Consortium showed nominal association with clinically defined hypomagnesemia, two showed association with kidney function, two with bone mineral density, and one of these also associated with fasting glucose levels. Common variants in CNNM2, a magnesium transporter studied only in model systems to date, as well as in CNNM3 and CNNM4, were also associated with magnesium concentrations in this study. We observed no associations with serum sodium or potassium levels exceeding p<4 x 10(-7). Follow-up studies of newly implicated genomic loci may provide additional insights into the regulation and homeostasis of human serum magnesium levels.
Keywords: Adult; Aged; European Continental Ancestry Group; Female; Genome-Wide Association Study; Humans; Magnesium; Male; Middle Aged; Polymorphism, Single Nucleotide; Potassium; Sodium

Genome-wide association study of PR interval. - Pfeufer, Arne; van Noord, Charlotte; Marciante, Kristin D; Arking, Dan E; Larson, Martin G; Smith, Albert Vernon; Tarasov, Kirill V; Müller, Martina; Sotoodehnia, Nona; Sinner, Moritz F; Verwoert, Germaine C; Li, Man; et al. (Nat Genet, 2010)
The electrocardiographic PR interval (or PQ interval) reflects atrial and atrioventricular nodal conduction, disturbances of which increase risk of atrial fibrillation. We report a meta-analysis of genome-wide association studies for PR interval from seven population-based European studies in the CHARGE Consortium: AGES, ARIC, CHS, FHS, KORA, Rotterdam Study, and SardiNIA (N = 28,517). We identified nine loci associated with PR interval at P < 5 x 10(-8). At the 3p22.2 locus, we observed two independent associations in voltage-gated sodium channel genes, SCN10A and SCN5A. Six of the loci were near cardiac developmental genes, including CAV1-CAV2, NKX2-5 (CSX1), SOX5, WNT11, MEIS1, and TBX5-TBX3, providing pathophysiologically interesting candidate genes. Five of the loci, SCN5A, SCN10A, NKX2-5, CAV1-CAV2, and SOX5, were also associated with atrial fibrillation (N = 5,741 cases, P < 0.0056). This suggests a role for common variation in ion channel and developmental genes in atrial and atrioventricular conduction as well as in susceptibility to atrial fibrillation.
Keywords: Aged; Atrial Fibrillation; Cohort Studies; Electrocardiography; Female; Genetic Loci; Genetic Predisposition to Disease; Genome-Wide Association Study; Heart Conduction System; Humans; Male; Meta-Analysis as Topic

Genome-wide meta-analysis increases to 71 the number of confirmed Crohn's disease susceptibility loci. - Franke, Andre; McGovern, Dermot P B; Barrett, Jeffrey C; Wang, Kai; Radford-Smith, Graham L; Ahmad, Tariq; Lees, Charlie W; Balschun, Tobias; Lee, James; Roberts, Rebecca; Anderson, Carl A; Bis, Joshua C; et al. (Nat Genet, 2010)
We undertook a meta-analysis of six Crohn's disease genome-wide association studies (GWAS) comprising 6,333 affected individuals (cases) and 15,056 controls and followed up the top association signals in 15,694 cases, 14,026 controls and 414 parent-offspring trios. We identified 30 new susceptibility loci meeting genome-wide significance (P < 5 × 10⁻⁸). A series of in silico analyses highlighted particular genes within these loci and, together with manual curation, implicated functionally interesting candidate genes including SMAD3, ERAP2, IL10, IL2RA, TYK2, FUT2, DNMT3A, DENND1B, BACH2 and TAGAP. Combined with previously confirmed loci, these results identify 71 distinct loci with genome-wide significant evidence for association with Crohn's disease.
Keywords: Computational Biology; Crohn Disease; Genetic Linkage; Genetic Loci; Genetic Predisposition to Disease; Genetic Variation; Genome, Human; Genome-Wide Association Study; Humans; Reproducibility of Results

Genomic variation associated with mortality among adults of European and African ancestry with heart failure: the cohorts for heart and aging research in genomic epidemiology consortium. - Morrison, Alanna C; Felix, Janine F; Cupples, L Adrienne; Glazer, Nicole L; Loehr, Laura R; Dehghan, Abbas; Demissie, Serkalem; Bis, Joshua C; Rosamond, Wayne D; Aulchenko, Yurii S; Wang, Ying A; Haritunians, Talin; et al. (Circ Cardiovasc Genet, 2010)
BACKGROUND: Prognosis and survival are significant concerns for individuals with heart failure (HF). To better understand the pathophysiology of HF prognosis, the association between 2,366,858 single-nucleotide polymorphisms (SNPs) and all-cause mortality was evaluated among individuals with incident HF from 4 community-based prospective cohorts: the Atherosclerosis Risk in Communities Study, the Cardiovascular Health Study, the Framingham Heart Study, and the Rotterdam Study. METHODS AND RESULTS: Participants were 2526 individuals of European ancestry and 466 individuals of African ancestry who experienced an incident HF event during follow-up in the respective cohorts. Within each study, the association between genetic variants and time to mortality among individuals with HF was assessed by Cox proportional hazards models that included adjustment for sex and age at the time of the HF event. Prospective fixed-effect meta-analyses were conducted for the 4 study populations of European ancestry (N=1645 deaths) and for the 2 populations of African ancestry (N=281 deaths). Genome-wide significance was set at P=5.0x10(-7). Meta-analytic findings among individuals of European ancestry revealed 1 genome-wide significant locus on chromosome 3p22 in an intron of CKLF-like MARVEL transmembrane domain containing 7 (CMTM7, P=3.2x10(-7)). Eight additional loci in individuals of European ancestry and 4 loci in individuals of African ancestry were identified by high-signal SNPs (P<1.0x10(-5)) but did not meet genome-wide significance. CONCLUSIONS: This study identified a novel locus associated with all-cause mortality among individuals of European ancestry with HF. This finding warrants additional investigation, including replication, in other studies of HF.
Keywords: African Americans; Aged; Aged, 80 and over; Chemokines; Cohort Studies; European Continental Ancestry Group; Female; Genome-Wide Association Study; Genotype; Heart Failure; Humans; Introns; Male; MARVEL Domain-Containing Proteins; Membrane Proteins; Middle Aged; Polymorphism, Single Nucleotide; Risk Factors

Hundreds of variants clustered in genomic loci and biological pathways affect human height. - Lango Allen, Hana; Estrada, Karol; Lettre, Guillaume; Berndt, Sonja I; Weedon, Michael N; Rivadeneira, Fernando; Willer, Cristen J; Jackson, Anne U; Vedantam, Sailaja; Raychaudhuri, Soumya; Ferreira, Teresa; Wood, Andrew R; et al. (Nature, 2010)
Most common human traits and diseases have a polygenic pattern of inheritance: DNA sequence variants at many genetic loci influence the phenotype. Genome-wide association (GWA) studies have identified more than 600 variants associated with human traits, but these typically explain small fractions of phenotypic variation, raising questions about the use of further studies. Here, using 183,727 individuals, we show that hundreds of genetic variants, in at least 180 loci, influence adult height, a highly heritable and classic polygenic trait. The large number of loci reveals patterns with important implications for genetic studies of common human diseases and traits. First, the 180 loci are not random, but instead are enriched for genes that are connected in biological pathways (P = 0.016) and that underlie skeletal growth defects (P < 0.001). Second, the likely causal gene is often located near the most strongly associated variant: in 13 of 21 loci containing a known skeletal growth gene, that gene was closest to the associated variant. Third, at least 19 loci have multiple independently associated variants, suggesting that allelic heterogeneity is a frequent feature of polygenic traits, that comprehensive explorations of already-discovered loci should discover additional variants and that an appreciable fraction of associated loci may have been identified. Fourth, associated variants are enriched for likely functional effects on genes, being over-represented among variants that alter amino-acid structure of proteins and expression levels of nearby genes. Our data explain approximately 10% of the phenotypic variation in height, and we estimate that unidentified common variants of similar effect sizes would increase this figure to approximately 16% of phenotypic variation (approximately 20% of heritable variation). Although additional approaches are needed to dissect the genetic architecture of polygenic human traits fully, our findings indicate that GWA studies can identify large numbers of loci that implicate biologically relevant genes and pathways.
Keywords: Body Height; Chromosomes, Human, Pair 3; Genetic Loci; Genetic Predisposition to Disease; Genome, Human; Genome-Wide Association Study; Humans; Metabolic Networks and Pathways; Multifactorial Inheritance; Phenotype; Polymorphism, Single Nucleotide

Independent susceptibility markers for atrial fibrillation on chromosome 4q25. - Lubitz, Steven A; Sinner, Moritz F; Lunetta, Kathryn L; Makino, Seiko; Pfeufer, Arne; Rahman, Rosanna; Veltman, Caroline E; Barnard, John; Bis, Joshua C; Danik, Stephan P; Sonni, Akshata; Shea, Marisa A; et al. (Circulation, 2010)
BACKGROUND: Genetic variants on chromosome 4q25 are associated with atrial fibrillation (AF). We sought to determine whether there is more than 1 susceptibility signal at this locus. METHODS AND RESULTS: Thirty-four haplotype-tagging single-nucleotide polymorphisms (SNPs) at the 4q25 locus were genotyped in 790 case and 1177 control subjects from Massachusetts General Hospital and tested for association with AF. We replicated SNPs associated with AF after adjustment for the most significantly associated SNP in 5066 case and 30 661 referent subjects from the German Competence Network for Atrial Fibrillation, Atherosclerosis Risk In Communities Study, Cleveland Clinic Lone AF Study, Cardiovascular Health Study, and Rotterdam Study. All subjects were of European ancestry. A multimarker risk score composed of SNPs that tagged distinct AF susceptibility signals was constructed and tested for association with AF, and all results were subjected to meta-analysis. The previously reported SNP, rs2200733, was most significantly associated with AF (minor allele odds ratio 1.80, 95% confidence interval 1.50 to 2.15, P=1.2 x 10(-20)) in the discovery sample. Adjustment for rs2200733 genotype revealed 2 additional susceptibility signals marked by rs17570669 and rs3853445. A graded risk of AF was observed with an increasing number of AF risk alleles at SNPs that tagged these 3 susceptibility signals. CONCLUSIONS: We identified 2 novel AF susceptibility signals on chromosome 4q25. Consideration of multiple susceptibility signals at chromosome 4q25 identifies individuals with an increased risk of AF and may localize regulatory elements at the locus with biological relevance in the pathogenesis of AF.
Keywords: Aged; Aged, 80 and over; Atrial Fibrillation; Chromosome Mapping; Chromosomes, Human, Pair 4; European Continental Ancestry Group; Female; Genetic Markers; Genetic Predisposition to Disease; Haplotypes; Humans; Male; Middle Aged; Polymorphism, Single Nucleotide; Risk Factors

Interactions of dietary whole-grain intake with fasting glucose- and insulin-related genetic loci in individuals of European descent: a meta-analysis of 14 cohort studies. - Nettleton, Jennifer A; McKeown, Nicola M; Kanoni, Stavroula; Lemaitre, Rozenn N; Hivert, Marie-France; Ngwa, Julius; van Rooij, Frank J A; Sonestedt, Emily; Wojczynski, Mary K; Ye, Zheng; Tanaka, Tosh; Garcia, Melissa; et al. (Diabetes Care, 2010)
OBJECTIVE: Whole-grain foods are touted for multiple health benefits, including enhancing insulin sensitivity and reducing type 2 diabetes risk. Recent genome-wide association studies (GWAS) have identified several single nucleotide polymorphisms (SNPs) associated with fasting glucose and insulin concentrations in individuals free of diabetes. We tested the hypothesis that whole-grain food intake and genetic variation interact to influence concentrations of fasting glucose and insulin. RESEARCH DESIGN AND METHODS: Via meta-analysis of data from 14 cohorts comprising ∼ 48,000 participants of European descent, we studied interactions of whole-grain intake with loci previously associated in GWAS with fasting glucose (16 loci) and/or insulin (2 loci) concentrations. For tests of interaction, we considered a P value <0.0028 (0.05 of 18 tests) as statistically significant. RESULTS: Greater whole-grain food intake was associated with lower fasting glucose and insulin concentrations independent of demographics, other dietary and lifestyle factors, and BMI (β [95% CI] per 1-serving-greater whole-grain intake: -0.009 mmol/l glucose [-0.013 to -0.005], P < 0.0001 and -0.011 pmol/l [ln] insulin [-0.015 to -0.007], P = 0.0003). No interactions met our multiple testing-adjusted statistical significance threshold. The strongest SNP interaction with whole-grain intake was rs780094 (GCKR) for fasting insulin (P = 0.006), where greater whole-grain intake was associated with a smaller reduction in fasting insulin concentrations in those with the insulin-raising allele. CONCLUSIONS: Our results support the favorable association of whole-grain intake with fasting glucose and insulin and suggest a potential interaction between variation in GCKR and whole-grain intake in influencing fasting insulin concentrations.
Keywords: Adult; Aged; Blood Glucose; Edible Grain; European Continental Ancestry Group; Fasting; Female; Genetic Loci; Genome-Wide Association Study; Genotype; Humans; Insulin; Male; Middle Aged; Polymorphism, Single Nucleotide

Large-scale genomic studies reveal central role of ABO in sP-selectin and sICAM-1 levels. - Barbalic, Maja; Dupuis, Josée; Dehghan, Abbas; Bis, Joshua C; Hoogeveen, Ron C; Schnabel, Renate B; Nambi, Vijay; Bretler, Monique; Smith, Nicholas L; Peters, Annette; Lu, Chen; Tracy, Russell P; et al. (Hum Mol Genet, 2010)
P-selectin and intercellular adhesion molecule-1 (ICAM-1) participate in inflammatory processes by promoting adhesion of leukocytes to vascular wall endothelium. Their soluble levels have been associated with adverse cardiovascular events. To identify loci affecting soluble levels of P-selectin (sP-selectin) and ICAM-1 (sICAM-1), we performed a genome-wide association study in a sample of 4115 (sP-selectin) and 9813 (sICAM-1) individuals of European ancestry as a part of The Cohorts for Heart and Aging Research in Genome Epidemiology consortium. The most significant SNP association for sP-selectin was within the SELP gene (rs6136, P = 4.05 x 10(-61)) and for sICAM-1 levels within the ICAM-1 gene (rs3093030, P = 3.53 x 10(-23)). Both sP-selectin and sICAM-1 were associated with ABO gene variants (rs579459, P = 1.86 x 10(-41) and rs649129, P = 1.22 x 10(-15), respectively) and in both cases the observed associations could be accounted for by the A1 allele of the ABO blood group. The absence of an association between ABO blood group and platelet-bound P-selectin levels in an independent subsample (N = 1088) from the ARIC study, suggests that the ABO blood group may influence cleavage of the P-selectin protein from the cell surface or clearance from the circulation, rather than its production and cellular presentation. These results provide new insights into adhesion molecule biology.
Keywords: ABO Blood-Group System; Blood Platelets; Enzyme-Linked Immunosorbent Assay; European Continental Ancestry Group; Fluorescence; Genome-Wide Association Study; Humans; Intercellular Adhesion Molecule-1; P-Selectin

Lipoprotein-associated phospholipase A(2) and risk of coronary disease, stroke, and mortality: collaborative analysis of 32 prospective studies. - Thompson, Alexander; Gao, Pei; Orfei, Lia; Watson, Sarah; Di Angelantonio, Emanuele; Kaptoge, Stephen; Ballantyne, Christie; Cannon, Christopher P; Criqui, Michael; Cushman, Mary; Hofman, Albert; Packard, Chris; et al. (Lancet, 2010)
BACKGROUND: Lipoprotein-associated phospholipase A(2) (Lp-PLA(2)), an inflammatory enzyme expressed in atherosclerotic plaques, is a therapeutic target being assessed in trials of vascular disease prevention. We investigated associations of circulating Lp-PLA(2) mass and activity with risk of coronary heart disease, stroke, and mortality under different circumstances. METHODS: With use of individual records from 79 036 participants in 32 prospective studies (yielding 17 722 incident fatal or non-fatal outcomes during 474 976 person-years at risk), we did a meta-analysis of within-study regressions to calculate risk ratios (RRs) per 1 SD higher value of Lp-PLA(2) or other risk factor. The primary outcome was coronary heart disease. FINDINGS: Lp-PLA(2) activity and mass were associated with each other (r=0.51, 95% CI 0.47-0.56) and proatherogenic lipids. We noted roughly log-linear associations of Lp-PLA(2) activity and mass with risk of coronary heart disease and vascular death. RRs, adjusted for conventional risk factors, were: 1.10 (95% CI 1.05-1.16) with Lp-PLA(2) activity and 1.11 (1.07-1.16) with Lp-PLA(2) mass for coronary heart disease; 1.08 (0.97-1.20) and 1.14 (1.02-1.27) for ischaemic stroke; 1.16 (1.09-1.24) and 1.13 (1.05-1.22) for vascular mortality; and 1.10 (1.04-1.17) and 1.10 (1.03-1.18) for non-vascular mortality, respectively. RRs with Lp-PLA(2) did not differ significantly in people with and without initial stable vascular disease, apart from for vascular death with Lp-PLA(2) mass. Adjusted RRs for coronary heart disease were 1.10 (1.02-1.18) with non-HDL cholesterol and 1.10 (1.00-1.21) with systolic blood pressure. INTERPRETATION: Lp-PLA(2) activity and mass each show continuous associations with risk of coronary heart disease, similar in magnitude to that with non-HDL cholesterol or systolic blood pressure in this population. Associations of Lp-PLA(2) mass and activity are not exclusive to vascular outcomes, and the vascular associations depend at least partly on lipids. FUNDING: UK Medical Research Council, GlaxoSmithKline, and British Heart Foundation.
Keywords: 1-Alkyl-2-acetylglycerophosphocholine Esterase; Blood Pressure; Coronary Disease; Female; Humans; Linear Models; Lipids; Male; Middle Aged; Prospective Studies; Risk Assessment; Risk Factors; Stroke; Systole

Meta-analyses of genome-wide association studies identify multiple loci associated with pulmonary function. - Hancock, Dana B; Eijgelsheim, Mark; Wilk, Jemma B; Gharib, Sina A; Loehr, Laura R; Marciante, Kristin D; Franceschini, Nora; van Durme, Yannick M T A; Chen, Ting-Hsu; Barr, R Graham; Schabath, Matthew B; Couper, David J; et al. (Nat Genet, 2010)
Spirometric measures of lung function are heritable traits that reflect respiratory health and predict morbidity and mortality. We meta-analyzed genome-wide association studies for two clinically important lung-function measures: forced expiratory volume in the first second (FEV(1)) and its ratio to forced vital capacity (FEV(1)/FVC), an indicator of airflow obstruction. This meta-analysis included 20,890 participants of European ancestry from four CHARGE Consortium studies: Atherosclerosis Risk in Communities, Cardiovascular Health Study, Framingham Heart Study and Rotterdam Study. We identified eight loci associated with FEV(1)/FVC (HHIP, GPR126, ADAM19, AGER-PPT2, FAM13A, PTCH1, PID1 and HTR4) and one locus associated with FEV(1) (INTS12-GSTCD-NPNT) at or near genome-wide significance (P < 5 x 10(-8)) in the CHARGE Consortium dataset. Our findings may offer insights into pulmonary function and pathogenesis of chronic lung disease.
Keywords: Databases, Genetic; Female; Forced Expiratory Volume; Genetic Predisposition to Disease; Genome, Human; Genome-Wide Association Study; Humans; Lung; Lung Diseases; Male; Meta-Analysis as Topic; Polymorphism, Single Nucleotide; Spirometry; Vital Capacity

Meta-analysis identifies 13 new loci associated with waist-hip ratio and reveals sexual dimorphism in the genetic basis of fat distribution. - Heid, Iris M; Jackson, Anne U; Randall, Joshua C; Winkler, Thomas W; Qi, Lu; Steinthorsdottir, Valgerdur; Thorleifsson, Gudmar; Zillikens, M Carola; Speliotes, Elizabeth K; Mägi, Reedik; Workalemahu, Tsegaselassie; White, Charles C; et al. (Nat Genet, 2010)
Waist-hip ratio (WHR) is a measure of body fat distribution and a predictor of metabolic consequences independent of overall adiposity. WHR is heritable, but few genetic variants influencing this trait have been identified. We conducted a meta-analysis of 32 genome-wide association studies for WHR adjusted for body mass index (comprising up to 77,167 participants), following up 16 loci in an additional 29 studies (comprising up to 113,636 subjects). We identified 13 new loci in or near RSPO3, VEGFA, TBX15-WARS2, NFE2L3, GRB14, DNM3-PIGC, ITPR2-SSPN, LY86, HOXC13, ADAMTS9, ZNRF3-KREMEN1, NISCH-STAB1 and CPEB4 (P = 1.9 × 10⁻⁹ to P = 1.8 × 10⁻⁴⁰) and the known signal at LYPLAL1. Seven of these loci exhibited marked sexual dimorphism, all with a stronger effect on WHR in women than men (P for sex difference = 1.9 × 10⁻³ to P = 1.2 × 10⁻¹³). These findings provide evidence for multiple loci that modulate body fat distribution independent of overall adiposity and reveal strong gene-by-sex interactions.
Keywords: Adipose Tissue; Age Factors; Chromosome Mapping; Female; Genome, Human; Genome-Wide Association Study; Humans; Male; Meta-Analysis as Topic; Polymorphism, Single Nucleotide; Sex Characteristics; Waist-Hip Ratio

A meta-analysis of four genome-wide association studies of survival to age 90 years or older: the Cohorts for Heart and Aging Research in Genomic Epidemiology Consortium. - Newman, Anne B; Walter, Stefan; Lunetta, Kathryn L; Garcia, Melissa E; Slagboom, P Eline; Christensen, Kaare; Arnold, Alice M; Aspelund, Thor; Aulchenko, Yurii S; Benjamin, Emelia J; Christiansen, Lene; D'Agostino, Ralph B; et al. (J Gerontol A Biol Sci Med Sci, 2010)
BACKGROUND: Genome-wide association studies (GWAS) may yield insights into longevity. METHODS: We performed a meta-analysis of GWAS in Caucasians from four prospective cohort studies: the Age, Gene/Environment Susceptibility-Reykjavik Study, the Cardiovascular Health Study, the Framingham Heart Study, and the Rotterdam Study participating in the Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) Consortium. Longevity was defined as survival to age 90 years or older (n = 1,836); the comparison group comprised cohort members who died between the ages of 55 and 80 years (n = 1,955). In a second discovery stage, additional genotyping was conducted in the Leiden Longevity Study cohort and the Danish 1905 cohort. RESULTS: There were 273 single-nucleotide polymorphism (SNP) associations with p < .0001, but none reached the prespecified significance level of 5 x 10(-8). Of the most significant SNPs, 24 were independent signals, and 16 of these SNPs were successfully genotyped in the second discovery stage, with one association for rs9664222, reaching 6.77 x 10(-7) for the combined meta-analysis of CHARGE and the stage 2 cohorts. The SNP lies in a region near MINPP1 (chromosome 10), a well-conserved gene involved in regulation of cellular proliferation. The minor allele was associated with lower odds of survival past age 90 (odds ratio = 0.82). Associations of interest in a homologue of the longevity assurance gene (LASS3) and PAPPA2 were not strengthened in the second stage. CONCLUSION: Survival studies of larger size or more extreme or specific phenotypes may support or refine these initial findings.
Keywords: Adult; Age Factors; Aged; Aged, 80 and over; Alleles; Cohort Studies; Confidence Intervals; Female; Genome-Wide Association Study; Genotype; Humans; Longevity; Male; Middle Aged; Odds Ratio; Polymorphism, Single Nucleotide

Multiple genetic loci influence serum urate levels and their relationship with gout and cardiovascular disease risk factors. - Yang, Qiong; Köttgen, Anna; Dehghan, Abbas; Smith, Albert V; Glazer, Nicole L; Chen, Ming-Huei; Chasman, Daniel I; Aspelund, Thor; Eiriksdottir, Gudny; Harris, Tamara B; Launer, Lenore; Nalls, Michael; et al. (Circ Cardiovasc Genet, 2010)
BACKGROUND: Elevated serum urate levels can lead to gout and are associated with cardiovascular risk factors. We performed a genome-wide association study to search for genetic susceptibility loci for serum urate and gout and investigated the causal nature of the associations of serum urate with gout and selected cardiovascular risk factors and coronary heart disease (CHD). METHODS AND RESULTS: Meta-analyses of genome-wide association studies (GWAS) were performed in 5 population-based cohorts of the Cohorts for Heart and Aging Research in Genome Epidemiology consortium for serum urate and gout in 28 283 white participants. The effect of the most significant single-nucleotide polymorphism at all genome-wide significant loci on serum urate was added to create a genetic urate score. Findings were replicated in the Women's Genome Health Study (n=22 054). Single-nucleotide polymorphisms at 8 genetic loci achieved genome-wide significance with serum urate levels (P=4×10(-8) to 2×10(-242) in SLC22A11, GCKR, R3HDM2-INHBC region, RREB1, PDZK1, SLC2A9, ABCG2, and SLC17A1). Only 2 loci (SLC2A9, ABCG2) showed genome-wide significant association with gout. The genetic urate score was strongly associated with serum urate and gout (odds ratio, 12.4 per 100 μmol/L; P=3×10(-39)) but not with blood pressure, glucose, estimated glomerular filtration rate, chronic kidney disease, or CHD. The lack of association between the genetic score and the latter phenotypes also was observed in the Women's Genome Health Study. CONCLUSIONS: The genetic urate score analysis suggested a causal relationship between serum urate and gout but did not provide evidence for one between serum urate and cardiovascular risk factors and CHD.
Keywords: Cardiovascular Diseases; Coronary Disease; Female; Genetic Loci; Genome-Wide Association Study; Gout; Humans; Male; Risk Factors; Uric Acid

New genetic loci implicated in fasting glucose homeostasis and their impact on type 2 diabetes risk. - Dupuis, Josée; Langenberg, Claudia; Prokopenko, Inga; Saxena, Richa; Soranzo, Nicole; Jackson, Anne U; Wheeler, Eleanor; Glazer, Nicole L; Bouatia-Naji, Nabila; Gloyn, Anna L; Lindgren, Cecilia M; Mägi, Reedik; et al. (Nat Genet, 2010)
Levels of circulating glucose are tightly regulated. To identify new loci influencing glycemic traits, we performed meta-analyses of 21 genome-wide association studies informative for fasting glucose, fasting insulin and indices of beta-cell function (HOMA-B) and insulin resistance (HOMA-IR) in up to 46,186 nondiabetic participants. Follow-up of 25 loci in up to 76,558 additional subjects identified 16 loci associated with fasting glucose and HOMA-B and two loci associated with fasting insulin and HOMA-IR. These include nine loci newly associated with fasting glucose (in or near ADCY5, MADD, ADRA2A, CRY2, FADS1, GLIS3, SLC2A2, PROX1 and C2CD4B) and one influencing fasting insulin and HOMA-IR (near IGF1). We also demonstrated association of ADCY5, PROX1, GCK, GCKR and DGKB-TMEM195 with type 2 diabetes. Within these loci, likely biological candidate genes influence signal transduction, cell proliferation, development, glucose-sensing and circadian regulation. Our results demonstrate that genetic studies of glycemic traits can identify type 2 diabetes risk loci, as well as loci containing gene variants that are associated with a modest elevation in glucose levels but are not associated with overt diabetes.
Keywords: Adolescent; Adult; Alleles; Blood Glucose; Child; Databases, Genetic; Diabetes Mellitus, Type 2; DNA Copy Number Variations; Fasting; Gene Expression Regulation; Genetic Loci; Genetic Predisposition to Disease; Genome-Wide Association Study; Homeostasis; Humans; Meta-Analysis as Topic; Polymorphism, Single Nucleotide; Quantitative Trait Loci; Quantitative Trait, Heritable; Reproducibility of Results

New loci associated with kidney function and chronic kidney disease. - Köttgen, Anna; Pattaro, Cristian; Böger, Carsten A; Fuchsberger, Christian; Olden, Matthias; Glazer, Nicole L; Parsa, Afshin; Gao, Xiaoyi; Yang, Qiong; Smith, Albert V; O'Connell, Jeffrey R; Li, Man; et al. (Nat Genet, 2010)
Chronic kidney disease (CKD) is a significant public health problem, and recent genetic studies have identified common CKD susceptibility variants. The CKDGen consortium performed a meta-analysis of genome-wide association data in 67,093 individuals of European ancestry from 20 predominantly population-based studies in order to identify new susceptibility loci for reduced renal function as estimated by serum creatinine (eGFRcrea), serum cystatin c (eGFRcys) and CKD (eGFRcrea < 60 ml/min/1.73 m(2); n = 5,807 individuals with CKD (cases)). Follow-up of the 23 new genome-wide-significant loci (P < 5 x 10(-8)) in 22,982 replication samples identified 13 new loci affecting renal function and CKD (in or near LASS2, GCKR, ALMS1, TFDP2, DAB2, SLC34A1, VEGFA, PRKAG2, PIP5K1B, ATXN2, DACH1, UBE2Q2 and SLC7A9) and 7 loci suspected to affect creatinine production and secretion (CPS1, SLC22A2, TMEM60, WDR37, SLC6A13, WDR72 and BCAS3). These results further our understanding of the biologic mechanisms of kidney function by identifying loci that potentially influence nephrogenesis, podocyte function, angiogenesis, solute transport and metabolic functions of the kidney.
Keywords: Cohort Studies; Creatinine; Cystatin C; Diet; Europe; Genetic Markers; Genome-Wide Association Study; Glomerular Filtration Rate; Humans; Kidney; Kidney Failure, Chronic; Models, Genetic; Risk Factors

Novel associations of multiple genetic loci with plasma levels of factor VII, factor VIII, and von Willebrand factor: The CHARGE (Cohorts for Heart and Aging Research in Genome Epidemiology) Consortium. - Smith, Nicholas L; Chen, Ming-Huei; Dehghan, Abbas; Strachan, David P; Basu, Saonli; Soranzo, Nicole; Hayward, Caroline; Rudan, Igor; Sabater-Lleal, Maria; Bis, Joshua C; de Maat, Moniek P M; Rumley, Ann; et al. (Circulation, 2010)
BACKGROUND: Plasma levels of coagulation factors VII (FVII), VIII (FVIII), and von Willebrand factor (vWF) influence risk of hemorrhage and thrombosis. We conducted genome-wide association studies to identify new loci associated with plasma levels. METHODS AND RESULTS: The setting of the study included 5 community-based studies for discovery comprising 23 608 European-ancestry participants: Atherosclerosis Risk In Communities Study, Cardiovascular Health Study, British 1958 Birth Cohort, Framingham Heart Study, and Rotterdam Study. All subjects had genome-wide single-nucleotide polymorphism (SNP) scans and at least 1 phenotype measured: FVII activity/antigen, FVIII activity, and vWF antigen. Each study used its genotype data to impute to HapMap SNPs and independently conducted association analyses of hemostasis measures using an additive genetic model. Study findings were combined by meta-analysis. Replication was conducted in 7604 participants not in the discovery cohort. For FVII, 305 SNPs exceeded the genome-wide significance threshold of 5.0x10(-8) and comprised 5 loci on 5 chromosomes: 2p23 (smallest P value 6.2x10(-24)), 4q25 (3.6x10(-12)), 11q12 (2.0x10(-10)), 13q34 (9.0x10(-259)), and 20q11.2 (5.7x10(-37)). Loci were within or near genes, including 4 new candidate genes and F7 (13q34). For vWF, 400 SNPs exceeded the threshold and marked 8 loci on 6 chromosomes: 6q24 (1.2x10(-22)), 8p21 (1.3x10(-16)), 9q34 (<5.0x10(-324)), 12p13 (1.7x10(-32)), 12q23 (7.3x10(-10)), 12q24.3 (3.8x10(-11)), 14q32 (2.3x10(-10)), and 19p13.2 (1.3x10(-9)). All loci were within genes, including 6 new candidate genes, as well as ABO (9q34) and VWF (12p13). For FVIII, 5 loci were identified and overlapped vWF findings. Nine of the 10 new findings were replicated. CONCLUSIONS: New genetic associations were discovered outside previously known biological pathways and may point to novel prevention and treatment targets of hemostasis disorders.
Keywords: Adult; Factor VII; Factor VIII; Female; Genome-Wide Association Study; Hemostasis; Humans; Male; Middle Aged; Phenotype; Polymorphism, Single Nucleotide; Thrombosis; von Willebrand Factor

Obesity is linked with lower brain volume in 700 AD and MCI patients. - Ho, April J; Raji, Cyrus A; Becker, James T; Lopez, Oscar L; Kuller, Lewis H; Hua, Xue; Lee, Suh; Hibar, Derrek; Dinov, Ivo D; Stein, Jason L; Jack, Clifford R; Weiner, Michael W; et al. (Neurobiol Aging, 2010)
Obesity is associated with lower brain volumes in cognitively normal elderly subjects, but no study has yet investigated the effects of obesity on brain structure in patients with mild cognitive impairment (MCI) or Alzheimer's disease (AD). To determine if higher body mass index (BMI) is associated with brain volume deficits in cognitively impaired elderly subjects, we analyzed brain magnetic resonance imaging (MRI) scans of 700 MCI or AD patients from 2 different cohorts: the Alzheimer's Disease Neuroimaging Initiative (ADNI) and the Cardiovascular Health Study-Cognition Study (CHS-CS). Tensor-based morphometry (TBM) was used to create 3-dimensional maps of regional tissue excess or deficits in subjects with MCI (ADNI, n = 399; CHS-CS, n = 77) and AD (ADNI, n = 188; CHS, n = 36). In both AD and MCI groups, higher body mass index was associated with brain volume deficits in frontal, temporal, parietal, and occipital lobes; the atrophic pattern was consistent in both ADNI and CHS populations. Cardiovascular risk factors, especially obesity, should be considered as influencing brain structure in those already afflicted by cognitive impairment and dementia.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Atrophy; Body Mass Index; Brain; Cognition Disorders; Cohort Studies; Female; Humans; Longitudinal Studies; Magnetic Resonance Imaging; Male; Obesity; Organ Size; Prospective Studies; Risk Factors

Obstructive sleep apnea-hypopnea and incident stroke: the sleep heart health study. - Redline, Susan; Yenokyan, Gayane; Gottlieb, Daniel J; Shahar, Eyal; O'Connor, George T; Resnick, Helaine E; Diener-West, Marie; Sanders, Mark H; Wolf, Philip A; Geraghty, Estella M; Ali, Tauqeer; Lebowitz, Michael; et al. (Am J Respir Crit Care Med, 2010)
RATIONALE: Although obstructive sleep apnea is associated with physiological perturbations that increase risk of hypertension and are proatherogenic, it is uncertain whether sleep apnea is associated with increased stroke risk in the general population. OBJECTIVES: To quantify the incidence of ischemic stroke with sleep apnea in a community-based sample of men and women across a wide range of sleep apnea. METHODS: Baseline polysomnography was performed between 1995 and 1998 in a longitudinal cohort study. The primary exposure was the obstructive apnea-hypopnea index (OAHI) and outcome was incident ischemic stroke. MEASUREMENTS AND MAIN RESULTS: A total of 5,422 participants without a history of stroke at the baseline examination and untreated for sleep apnea were followed for a median of 8.7 years. One hundred ninety-three ischemic strokes were observed. In covariate-adjusted Cox proportional hazard models, a significant positive association between ischemic stroke and OAHI was observed in men (P value for linear trend: P = 0.016). Men in the highest OAHI quartile (>19) had an adjusted hazard ratio of 2.86 (95% confidence interval, 1.1-7.4). In the mild to moderate range (OAHI, 5-25), each one-unit increase in OAHI in men was estimated to increase stroke risk by 6% (95% confidence interval, 2-10%). In women, stroke was not significantly associated with OAHI quartiles, but increased risk was observed at an OAHI greater than 25. CONCLUSIONS: The strong adjusted association between ischemic stroke and OAHI in community-dwelling men with mild to moderate sleep apnea suggests that this is an appropriate target for future stroke prevention trials.
Keywords: Aged; Female; Humans; Longitudinal Studies; Male; Middle Aged; Polysomnography; Proportional Hazards Models; Prospective Studies; Severity of Illness Index; Sex Factors; Sleep Apnea, Obstructive; Stroke

Polymorphisms in the mitochondrial DNA control region and frailty in older adults. - Moore, Ann Z; Biggs, Mary L; Matteini, Amy; O'Connor, Ashley; McGuire, Sarah; Beamer, Brock A; Fallin, M Danielle; Fried, Linda P; Walston, Jeremy; Chakravarti, Aravinda; Arking, Dan E (PLoS One, 2010)
BACKGROUND: Mitochondria contribute to the dynamics of cellular metabolism, the production of reactive oxygen species, and apoptotic pathways. Consequently, mitochondrial function has been hypothesized to influence functional decline and vulnerability to disease in later life. Mitochondrial genetic variation may contribute to altered susceptibility to the frailty syndrome in older adults. METHODOLOGY/PRINCIPAL FINDINGS: To assess potential mitochondrial genetic contributions to the likelihood of frailty, mitochondrial DNA (mtDNA) variation was compared in frail and non-frail older adults. Associations of selected SNPs with a muscle strength phenotype were also explored. Participants were selected from the Cardiovascular Health Study (CHS), a population-based observational study (1989-1990, 1992-1993). At baseline, frailty was identified as the presence of three or more of five indicators (weakness, slowness, shrinking, low physical activity, and exhaustion). mtDNA variation was assessed in a pilot study, including 315 individuals selected as extremes of the frailty phenotype, using an oligonucleotide sequencing microarray based on the Revised Cambridge Reference Sequence. Three mtDNA SNPs were statistically significantly associated with frailty across all pilot participants or in sex-stratified comparisons: mt146, mt204, and mt228. In addition to pilot participants, 4,459 additional men and women with frailty classifications, and an overlapping subset of 4,453 individuals with grip strength measurements, were included in the study population genotyped at mt204 and mt228. In the study population, the mt204 C allele was associated with greater likelihood of frailty (adjusted odds ratio = 2.04, 95% CI = 1.07-3.60, p = 0.020) and lower grip strength (adjusted coefficient = -2.04, 95% CI = -3.33- -0.74, p = 0.002). CONCLUSIONS: This study supports a role for mitochondrial genetic variation in the frailty syndrome and later life muscle strength, demonstrating the importance of the mitochondrial genome in complex geriatric phenotypes.
Keywords: Aged; Aged, 80 and over; DNA, Mitochondrial; Female; Frail Elderly; Genotype; Humans; Male; Polymorphism, Genetic

Reproductive history, hormone replacement, and incidence of venous thromboembolism: the Longitudinal Investigation of Thromboembolism Etiology. - Ohira, Tetsuya; Folsom, Aaron R; Cushman, Mary; White, Richard H; Hannan, Peter J; Rosamond, Wayne D; Heckbert, Susan R (Br J Haematol, 2010)
Numerous studies have established that hormone replacement therapy increases the risk of venous thromboembolism (VTE), but an association of endogenous oestrogen exposure with the incidence of VTE is not fully established. Using a prospective design combining the Atherosclerosis Risk in Communities and the Cardiovascular Health Study cohort, we studied the 12-year risk of VTE in relation to hormone replacement therapy use, age at menopause, parity number, and type of menopause in 8236 post-menopausal women. There were no significant associations of age at menopause, parity number, or type of menopause with incidence of VTE. Women currently using hormone replacement had a 1.6-times higher multivariate-adjusted rate ratio (RR) of VTE compared with those without hormone use in the time-dependent model (RR=1.60, 95% confidence interval [CI], 1.06-2.36; Population attributable fraction=6.7%, 95%CI, 1.0-10.3). When we excluded women with 1-year or more duration of hormone therapy at baseline, the association was stronger (RR=2.02, 95%CI, 1.31-3.12). The multivariate-adjusted RRs of VTE for current users tended to be higher in those with idiopathic VTE (RR=2.40, 95%CI, 1.40-4.12) than those with secondary VTE (RR=1.08, 95%CI, 0.63-1.85). Hormone replacement therapy is associated with increased risk of VTE, but reproductive history markers of endogenous oestrogen exposure were not associated with VTE.
Keywords: Age Factors; Aged; Epidemiologic Methods; Estrogen Replacement Therapy; Female; Humans; Male; Middle Aged; Parity; Pregnancy; Reproductive History; United States; Venous Thromboembolism

Sleep disturbances, quality of life, and ethnicity: the Sleep Heart Health Study. - Baldwin, Carol M; Ervin, Ann-Margret; Mays, Mary Z; Robbins, John; Shafazand, Shirin; Walsleben, Joyce; Weaver, Terri (J Clin Sleep Med, 2010)
STUDY OBJECTIVES: To compare health-related quality of life (HR-QOL) across subgroups defined by sleep disturbances and ethnicity. METHODS: Men (47%) and women (53%) Sleep Heart Health Study participants age 40 and older (N = 5237) underwent overnight polysomnography and completed self-report questionnaires on symptoms of sleep disturbances. The physical and mental composite scales (PCS and MCS) of the Medical Outcomes Study 36-item short form survey assessed HR-QOL and were compared to sleep data. RESULTS: Participants self-identified as Caucasian/White (n = 4482, 86%), African American/Black (n = 490, 9%), or Hispanic/Mexican American (n = 265, 5%). The prevalence of obstructive sleep apnea (OSA) was 17%, frequent snoring was 34%, difficulty initiating or maintaining sleep (DIMS; insomnia symptoms) was 30%, and excessive daytime sleepiness (EDS) was 25%. African American participants with frequent snoring, insomnia symptoms, or EDS had significantly poorer physical health compared to Caucasians (p < 0.001). Hispanics with frequent snoring, insomnia symptoms, or EDS had significantly poorer mental health than Caucasian participants (p <0.001). Neither PCS nor MCS scores differed significantly across ethnic subgroups for participants with moderate to severe OSA (respiratory disturbance index > 15, 4% desaturation). CONCLUSIONS: Across ethnic/racial subgroups, sleep disturbances are associated with worse physical and better mental HR-QOL than the U.S. norm, but this relationship may be moderated by comorbid health conditions. This study replicates and extends prior research indicating differences among minority and non-minority participants and highlights the need for future studies of sleep disturbances with larger samples of minorities that control for comorbid health conditions.
Keywords: African Americans; Cohort Studies; Ethnic Groups; European Continental Ancestry Group; Female; Health Status; Heart Diseases; Hispanic Americans; Humans; Longitudinal Studies; Male; Mental Health; Middle Aged; Polysomnography; Prevalence; Quality of Life; Sleep Apnea, Obstructive; Sleep Initiation and Maintenance Disorders; Sleep Wake Disorders; Snoring; Surveys and Questionnaires; United States

Study of the relationship between the interleukin-6 gene and obstructive sleep apnea. - Larkin, Emma K; Patel, Sanjay R; Zhu, Xiaofeng; Tracy, Russell P; Jenny, Nancy S; Reiner, Alex P; Walston, Jeremy; Redline, Susan (Clin Transl Sci, 2010)
Keywords: Adult; African Americans; Alleles; Female; Humans; Interleukin-6; Male; Middle Aged; Polymorphism, Single Nucleotide; Sleep Apnea, Obstructive

Subclinical hypothyroidism and the risk of coronary heart disease and mortality. - Rodondi, Nicolas; den Elzen, Wendy P J; Bauer, Douglas C; Cappola, Anne R; Razvi, Salman; Walsh, John P; Asvold, Bjørn O; Iervasi, Giorgio; Imaizumi, Misa; Collet, Tinh-Hai; Bremner, Alexandra; Maisonneuve, Patrick; et al. (JAMA, 2010)
CONTEXT: Data regarding the association between subclinical hypothyroidism and cardiovascular disease outcomes are conflicting among large prospective cohort studies. This might reflect differences in participants' age, sex, thyroid-stimulating hormone (TSH) levels, or preexisting cardiovascular disease. OBJECTIVE: To assess the risks of coronary heart disease (CHD) and total mortality for adults with subclinical hypothyroidism. DATA SOURCES AND STUDY SELECTION: The databases of MEDLINE and EMBASE (1950 to May 31, 2010) were searched without language restrictions for prospective cohort studies with baseline thyroid function and subsequent CHD events, CHD mortality, and total mortality. The reference lists of retrieved articles also were searched. DATA EXTRACTION: Individual data on 55,287 participants with 542,494 person-years of follow-up between 1972 and 2007 were supplied from 11 prospective cohorts in the United States, Europe, Australia, Brazil, and Japan. The risk of CHD events was examined in 25,977 participants from 7 cohorts with available data. Euthyroidism was defined as a TSH level of 0.50 to 4.49 mIU/L. Subclinical hypothyroidism was defined as a TSH level of 4.5 to 19.9 mIU/L with normal thyroxine concentrations. RESULTS: Among 55,287 adults, 3450 had subclinical hypothyroidism (6.2%) and 51,837 had euthyroidism. During follow-up, 9664 participants died (2168 of CHD), and 4470 participants had CHD events (among 7 studies). The risk of CHD events and CHD mortality increased with higher TSH concentrations. In age- and sex-adjusted analyses, the hazard ratio (HR) for CHD events was 1.00 (95% confidence interval [CI], 0.86-1.18) for a TSH level of 4.5 to 6.9 mIU/L (20.3 vs 20.3/1000 person-years for participants with euthyroidism), 1.17 (95% CI, 0.96-1.43) for a TSH level of 7.0 to 9.9 mIU/L (23.8/1000 person-years), and 1.89 (95% CI, 1.28-2.80) for a TSH level of 10 to 19.9 mIU/L (n = 70 events/235; 38.4/1000 person-years; P <.001 for trend). The corresponding HRs for CHD mortality were 1.09 (95% CI, 0.91-1.30; 5.3 vs 4.9/1000 person-years for participants with euthyroidism), 1.42 (95% CI, 1.03-1.95; 6.9/1000 person-years), and 1.58 (95% CI, 1.10-2.27, n = 28 deaths/333; 7.7/1000 person-years; P = .005 for trend). Total mortality was not increased among participants with subclinical hypothyroidism. Results were similar after further adjustment for traditional cardiovascular risk factors. Risks did not significantly differ by age, sex, or preexisting cardiovascular disease. CONCLUSIONS: Subclinical hypothyroidism is associated with an increased risk of CHD events and CHD mortality in those with higher TSH levels, particularly in those with a TSH concentration of 10 mIU/L or greater.
Keywords: Adolescent; Adult; Aged; Aged, 80 and over; Coronary Disease; Female; Humans; Hypothyroidism; Male; Middle Aged; Mortality; Prospective Studies; Risk; Thyrotropin; Young Adult

Triglyceride-mediated pathways and coronary disease: collaborative analysis of 101 studies. - Sarwar, Nadeem; Sandhu, Manjinder S; Ricketts, Sally L; Butterworth, Adam S; Di Angelantonio, Emanuele; Boekholdt, S Matthijs; Ouwehand, Willem; Watkins, Hugh; Samani, Nilesh J; Saleheen, Danish; Lawlor, Debbie; Reilly, Muredach P; et al. (Lancet, 2010)
BACKGROUND: Whether triglyceride-mediated pathways are causally relevant to coronary heart disease is uncertain. We studied a genetic variant that regulates triglyceride concentration to help judge likelihood of causality. METHODS: We assessed the -1131T>C (rs662799) promoter polymorphism of the apolipoprotein A5 (APOA5) gene in relation to triglyceride concentration, several other risk factors, and risk of coronary heart disease. We compared disease risk for genetically-raised triglyceride concentration (20,842 patients with coronary heart disease, 35,206 controls) with that recorded for equivalent differences in circulating triglyceride concentration in prospective studies (302 430 participants with no history of cardiovascular disease; 12,785 incident cases of coronary heart disease during 2.79 million person-years at risk). We analysed -1131T>C in 1795 people without a history of cardiovascular disease who had information about lipoprotein concentration and diameter obtained by nuclear magnetic resonance spectroscopy. FINDINGS: The minor allele frequency of -1131T>C was 8% (95% CI 7-9). -1131T>C was not significantly associated with several non-lipid risk factors or LDL cholesterol, and it was modestly associated with lower HDL cholesterol (mean difference per C allele 3.5% [95% CI 2.6-4.6]; 0.053 mmol/L [0.039-0.068]), lower apolipoprotein AI (1.3% [0.3-2.3]; 0.023 g/L [0.005-0.041]), and higher apolipoprotein B (3.2% [1.3-5.1]; 0.027 g/L [0.011-0.043]). By contrast, for every C allele inherited, mean triglyceride concentration was 16.0% (95% CI 12.9-18.7), or 0.25 mmol/L (0.20-0.29), higher (p=4.4x10(-24)). The odds ratio for coronary heart disease was 1.18 (95% CI 1.11-1.26; p=2.6x10(-7)) per C allele, which was concordant with the hazard ratio of 1.10 (95% CI 1.08-1.12) per 16% higher triglyceride concentration recorded in prospective studies. -1131T>C was significantly associated with higher VLDL particle concentration (mean difference per C allele 12.2 nmol/L [95% CI 7.7-16.7]; p=9.3x10(-8)) and smaller HDL particle size (0.14 nm [0.08-0.20]; p=7.0x10(-5)), factors that could mediate the effects of triglyceride. INTERPRETATION: These data are consistent with a causal association between triglyceride-mediated pathways and coronary heart disease. FUNDING: British Heart Foundation, UK Medical Research Council, Novartis.
Keywords: Apolipoprotein A-V; Apolipoproteins; Apolipoproteins A; Coronary Disease; Gene Frequency; Genotype; Humans; Lipids; Lipoproteins, HDL; Lipoproteins, LDL; Lipoproteins, VLDL; Mendelian Randomization Analysis; Particle Size; Polymorphism, Single Nucleotide; Promoter Regions, Genetic; Risk Factors; Triglycerides

Validation of an atrial fibrillation risk algorithm in whites and African Americans. - Schnabel, Renate B; Aspelund, Thor; Li, Guo; Sullivan, Lisa M; Suchy-Dicey, Astrid; Harris, Tamara B; Pencina, Michael J; D'Agostino, Ralph B; Levy, Daniel; Kannel, William B; Wang, Thomas J; Kronmal, Richard A; et al. (Arch Intern Med, 2010)
BACKGROUND: We sought to validate a recently published risk algorithm for incident atrial fibrillation (AF) in independent cohorts and other racial groups. METHODS: We evaluated the performance of a Framingham Heart Study (FHS)-derived risk algorithm modified for 5-year incidence of AF in the FHS (n = 4764 participants) and 2 geographically and racially diverse cohorts in the age range 45 to 95 years: AGES (the Age, Gene/Environment Susceptibility-Reykjavik Study) (n = 4238) and CHS (the Cardiovascular Health Study) (n = 5410, of whom 874 [16.2%] were African Americans). The risk algorithm included age, sex, body mass index, systolic blood pressure, electrocardiographic PR interval, hypertension treatment, and heart failure. RESULTS: We found 1359 incident AF events in 100 074 person-years of follow-up. Unadjusted 5-year event rates differed by cohort (AGES, 12.8 cases/1000 person-years; CHS whites, 22.7 cases/1000 person-years; and FHS, 4.5 cases/1000 person-years) and by race (CHS African Americans, 18.4 cases/1000 person-years). The strongest risk factors in all samples were age and heart failure. The relative risks for incident AF associated with risk factors were comparable across cohorts and race groups. After recalibration for baseline incidence and risk factor distribution, the Framingham algorithm, reported in C statistic, performed reasonably well in all samples: AGES, 0.67 (95% confidence interval [CI], 0.64-0.71); CHS whites, 0.68 (95% CI, 0.66-0.70); and CHS African Americans, 0.66 (95% CI, 0.61-0.71). Risk factors combined in the algorithm explained between 47.0% (AGES) and 63.6% (FHS) of the population-attributable risk. CONCLUSIONS: Risk of incident AF in community-dwelling whites and African Americans can be assessed reliably by routinely available and potentially modifiable clinical variables. Seven risk factors accounted for up to 64% of risk.
Keywords: African Continental Ancestry Group; Age Factors; Aged; Aged, 80 and over; Algorithms; Atrial Fibrillation; Blood Pressure; Body Mass Index; Cohort Studies; Electrocardiography; Europe; European Continental Ancestry Group; Female; Follow-Up Studies; Heart Failure; Humans; Hypertension; Incidence; Kaplan-Meier Estimate; Male; Middle Aged; Proportional Hazards Models; Risk Factors; Sex Factors; Systole; United States

Validation of the health ABC heart failure model for incident heart failure risk prediction: the Cardiovascular Health Study. - Kalogeropoulos, Andreas; Psaty, Bruce M; Vasan, Ramachandran S; Georgiopoulou, Vasiliki; Smith, Andrew L; Smith, Nicholas L; Kritchevsky, Stephen B; Wilson, Peter W F; Newman, Anne B; Harris, Tamara B; Butler, Javed (Circ Heart Fail, 2010)
BACKGROUND: The recently developed and internally validated Health ABC HF model uses 9 routinely available clinical variables to determine incident heart failure risk. In this study, we sought to externally validate the Health ABC HF model. METHODS AND RESULTS: Observed 5-year incidence of heart failure, defined as first hospitalization for new-onset heart failure, was compared with 5-year risk estimates derived from the Health ABC HF model among participants without heart failure at baseline in the Cardiovascular Health Study. During follow-up, 400 of 5335 (7.5%) participants developed heart failure over 5 years versus 364 (6.8%) predicted by the Health ABC HF model (predicted-to-observed ratio, 0.90). Observed versus predicted 5-year heart failure probabilities were 3.2% versus 2.8%, 9.0% versus 7.0%, 15.9% versus 13.7%, and 24.6% versus 30.8% for the <5%, 5% to 10%, 10% to 20%, and >20% 5-year risk categories, respectively. The Hosmer-Lemeshow chi(2) was 14.72 (degrees of freedom, 10; P=0.14), and the C index was 0.74 (95% CI, 0.72 to 0.76). Calibration and discrimination demonstrated adequate performance across sex and race overall; however, risk was underestimated in white men, especially in the 5% to 10% risk category. Model performance was optimal when participants with normal left ventricular function at baseline were assessed separately. Performance was consistent across age groups. Analyses with death as a competing risk yielded similar results. CONCLUSIONS: The Health ABC HF model adequately predicted 5-year heart failure risk in a large community-based study, providing support for the external validity of the model. This tool may be used to identify individuals to whom to target heart failure prevention efforts.
Keywords: Age Distribution; Aged; Aged, 80 and over; Cause of Death; Cohort Studies; Confidence Intervals; Disease Progression; Echocardiography, Doppler; Female; Heart Failure; Humans; Incidence; Male; Models, Statistical; Predictive Value of Tests; Prognosis; Severity of Illness Index; Sex Distribution; Survival Analysis; United States

Association of eGFR-Related Loci Identified by GWAS with Incident CKD and ESRD. - Böger, Carsten A; Gorski, Mathias; Li, Man; Hoffmann, Michael M; Huang, Chunmei; Yang, Qiong; Teumer, Alexander; Krane, Vera; O'Seaghdha, Conall M; Kutalik, Zoltán; Wichmann, H-Erich; Haak, Thomas; et al. (PLoS Genet, 2011)
Family studies suggest a genetic component to the etiology of chronic kidney disease (CKD) and end stage renal disease (ESRD). Previously, we identified 16 loci for eGFR in genome-wide association studies, but the associations of these single nucleotide polymorphisms (SNPs) for incident CKD or ESRD are unknown. We thus investigated the association of these loci with incident CKD in 26,308 individuals of European ancestry free of CKD at baseline drawn from eight population-based cohorts followed for a median of 7.2 years (including 2,122 incident CKD cases defined as eGFR <60ml/min/1.73m(2) at follow-up) and with ESRD in four case-control studies in subjects of European ancestry (3,775 cases, 4,577 controls). SNPs at 11 of the 16 loci (UMOD, PRKAG2, ANXA9, DAB2, SHROOM3, DACH1, STC1, SLC34A1, ALMS1/NAT8, UBE2Q2, and GCKR) were associated with incident CKD; p-values ranged from p = 4.1e-9 in UMOD to p = 0.03 in GCKR. After adjusting for baseline eGFR, six of these loci remained significantly associated with incident CKD (UMOD, PRKAG2, ANXA9, DAB2, DACH1, and STC1). SNPs in UMOD (OR = 0.92, p = 0.04) and GCKR (OR = 0.93, p = 0.03) were nominally associated with ESRD. In summary, the majority of eGFR-related loci are either associated or show a strong trend towards association with incident CKD, but have modest associations with ESRD in individuals of European descent. Additional work is required to characterize the association of genetic determinants of CKD and ESRD at different stages of disease progression.
Keywords: Adaptor Proteins, Signal Transducing; Adult; Aged; Chronic Disease; Creatinine; European Continental Ancestry Group; Female; Follow-Up Studies; Genetic Association Studies; Humans; Kidney Diseases; Kidney Failure, Chronic; Male; Middle Aged; Polymorphism, Single Nucleotide; Receptor, Epidermal Growth Factor; Uromodulin

The association of genetic variants in interleukin-1 genes with cognition: findings from the cardiovascular health study. - Benke, K S; Carlson, M C; Doan, B Q; Walston, J D; Xue, Q L; Reiner, A P; Fried, L P; Arking, D E; Chakravarti, A; Fallin, M D (Exp Gerontol, 2011)
The inflammatory cytokine interleukin-1 (IL1) potentially plays a role in cognitive deterioration through pathology due to a dementing disorder or due to an aging process. Study of genetic variants in the IL1 genes has been mostly limited to diseases such as Alzheimer's, however, there may be benefit to studying a continuous measure of cognition. Using data from the Cardiovascular Health Study, we evaluate genetic variation in the genes encoding inflammatory agonists IL1A and IL1B, and the antagonist IL1RN, with repeated measures of global cognition (3MS) and processing speed (DSST), using mixed effects models. We found statistically significant minor allele SNP associations with baseline performance on the 3MS in the IL1RN gene for Caucasians (rs17042917: beta=0.47, 95%CI=0.09, 0.85, p=0.016; rs4251961: beta=-0.36, 95%CI=-0.13,-0.60, p=0.0027; rs931471: beta=0.39, 95%CI=0.13, 0.65, p=0.0032), and the IL1B gene for African Americans (rs1143627: beta=1.6, 95%CI=0.48, 2.8; p=0.006 and rs1143634: beta=2.09, 95%CI=0.39, 3.8; p=0.016). Associations appear to be weaker in a subgroup with higher education level. Upon removing those diagnosed with dementia, effect sizes and statistical significance attenuated. These results provide supporting evidence that genetic variants in IL1 genes may be involved in inflammatory-related lowered cognition, that higher education may modify genetic predisposition, and that these associations may be driven by a dementia process.
Keywords: African Americans; Aged; Aged, 80 and over; Cognition; Cognition Disorders; Dementia; Educational Status; European Continental Ancestry Group; Female; Genetic Predisposition to Disease; Genetic Variation; Genotype; Humans; Interleukin 1 Receptor Antagonist Protein; Interleukin-1alpha; Interleukin-1beta; Linkage Disequilibrium; Longitudinal Studies; Male; Polymorphism, Single Nucleotide; Prospective Studies; Risk Factors; United States

Association of genetic variation with systolic and diastolic blood pressure among African Americans: the Candidate Gene Association Resource study. - Fox, Ervin R; Young, J Hunter; Li, Yali; Dreisbach, Albert W; Keating, Brendan J; Musani, Solomon K; Liu, Kiang; Morrison, Alanna C; Ganesh, Santhi; Kutlar, Abdullah; Ramachandran, Vasan S; Polak, Josef F; et al. (Hum Mol Genet, 2011)
The prevalence of hypertension in African Americans (AAs) is higher than in other US groups; yet, few have performed genome-wide association studies (GWASs) in AA. Among people of European descent, GWASs have identified genetic variants at 13 loci that are associated with blood pressure. It is unknown if these variants confer susceptibility in people of African ancestry. Here, we examined genome-wide and candidate gene associations with systolic blood pressure (SBP) and diastolic blood pressure (DBP) using the Candidate Gene Association Resource (CARe) consortium consisting of 8591 AAs. Genotypes included genome-wide single-nucleotide polymorphism (SNP) data utilizing the Affymetrix 6.0 array with imputation to 2.5 million HapMap SNPs and candidate gene SNP data utilizing a 50K cardiovascular gene-centric array (ITMAT-Broad-CARe [IBC] array). For Affymetrix data, the strongest signal for DBP was rs10474346 (P= 3.6 × 10(-8)) located near GPR98 and ARRDC3. For SBP, the strongest signal was rs2258119 in C21orf91 (P= 4.7 × 10(-8)). The top IBC association for SBP was rs2012318 (P= 6.4 × 10(-6)) near SLC25A42 and for DBP was rs2523586 (P= 1.3 × 10(-6)) near HLA-B. None of the top variants replicated in additional AA (n = 11 882) or European-American (n = 69 899) cohorts. We replicated previously reported European-American blood pressure SNPs in our AA samples (SH2B3, P= 0.009; TBX3-TBX5, P= 0.03; and CSK-ULK3, P= 0.0004). These genetic loci represent the best evidence of genetic influences on SBP and DBP in AAs to date. More broadly, this work supports that notion that blood pressure among AAs is a trait with genetic underpinnings but also with significant complexity.
Keywords: Adult; African Americans; Aged; Blood Pressure; Cohort Studies; Diastole; European Continental Ancestry Group; Female; Genetic Loci; Genome-Wide Association Study; Genotype; Humans; Hypertension; Male; Middle Aged; Phenotype; Polymorphism, Single Nucleotide; Systole

Association of genomic loci from a cardiovascular gene SNP array with fibrinogen levels in European Americans and African-Americans from six cohort studies: the Candidate Gene Association Resource (CARe). - Wassel, Christina L; Lange, Leslie A; Keating, Brendan J; Taylor, Kira C; Johnson, Andrew D; Palmer, Cameron; Ho, Lindsey A; Smith, Nicholas L; Lange, Ethan M; Li, Yun; Yang, Qiong; Delaney, Joseph A; et al. (Blood, 2011)
Several common genomic loci, involving various immunity- and metabolism-related genes, have been associated with plasma fibrinogen in European Americans (EAs). The genetic determinants of fibrinogen in African Americans (AAs) are poorly characterized. Using a vascular gene-centric array in 23,634 EA and 6657 AA participants from 6 studies comprising the Candidate Gene Association Resource project, we examined the association of 47,539 common and lower frequency variants with fibrinogen concentration. We identified a rare Pro265Leu variant in FGB (rs6054) associated with lower fibrinogen. Common fibrinogen gene single nucleotide polymorphisms (FGB rs1800787 and FGG rs2066861) significantly associated with fibrinogen in EAs were prevalent in AAs and showed consistent associations. Several fibrinogen locus single nucleotide polymorphism associated with lower fibrinogen were exclusive to AAs; these include a newly reported association with FGA rs10050257. For IL6R, IL1RN, and NLRP3 inflammatory gene loci, associations with fibrinogen were concordant between EAs and AAs, but not at other loci (CPS1, PCCB, and SCL22A5-IRF1). The association of FGG rs2066861 with fibrinogen differed according to assay type used to measure fibrinogen. Further characterization of common and lower-frequency genetic variants that contribute to interpopulation differences in fibrinogen phenotype may help refine our understanding of the contribution of hemostasis and inflammation to atherothrombotic risk.
Keywords: Adult; African Americans; Aged; Cardiovascular Diseases; Cohort Studies; European Continental Ancestry Group; Female; Fibrinogen; Genetic Predisposition to Disease; Haplotypes; Humans; Male; Middle Aged; Phenotype; Polymorphism, Single Nucleotide; Risk Factors

Association of hypertension drug target genes with blood pressure and hypertension in 86,588 individuals. - Johnson, Andrew D; Newton-Cheh, Christopher; Chasman, Daniel I; Ehret, Georg B; Johnson, Toby; Rose, Lynda; Rice, Kenneth; Verwoert, Germaine C; Launer, Lenore J; Gudnason, Vilmundur; Larson, Martin G; Chakravarti, Aravinda; et al. (Hypertension, 2011)
We previously conducted genome-wide association meta-analysis of systolic blood pressure, diastolic blood pressure, and hypertension in 29,136 people from 6 cohort studies in the Cohorts for Heart and Aging Research in Genomic Epidemiology Consortium. Here we examine associations of these traits with 30 gene regions encoding known antihypertensive drug targets. We find nominal evidence of association of ADRB1, ADRB2, AGT, CACNA1A, CACNA1C, and SLC12A3 polymorphisms with 1 or more BP traits in the Cohorts for Heart and Aging Research in Genomic Epidemiology genome-wide association meta-analysis. We attempted replication of the top meta-analysis single nucleotide polymorphisms for these genes in the Global BPgen Consortium (n=34,433) and the Women's Genome Health Study (n=23,019) and found significant results for rs1801253 in ADRB1 (Arg389Gly), with the Gly allele associated with a lower mean systolic blood pressure (β: 0.57 mm Hg; SE: 0.09 mm Hg; meta-analysis: P=4.7×10(-10)), diastolic blood pressure (β: 0.36 mm Hg; SE: 0.06 mm Hg; meta-analysis: P=9.5×10(-10)), and prevalence of hypertension (β: 0.06 mm Hg; SE: 0.02 mm Hg; meta-analysis: P=3.3×10(-4)). Variation in AGT (rs2004776) was associated with systolic blood pressure (β: 0.42 mm Hg; SE: 0.09 mm Hg; meta-analysis: P=3.8×10(-6)), as well as diastolic blood pressure (P=5.0×10(-8)) and hypertension (P=3.7×10(-7)). A polymorphism in ACE (rs4305) showed modest replication of association with increased hypertension (β: 0.06 mm Hg; SE: 0.01 mm Hg; meta-analysis: P=3.0×10(-5)). Two loci, ADRB1 and AGT, contain single nucleotide polymorphisms that reached a genome-wide significance threshold in meta-analysis for the first time. Our findings suggest that these genes warrant further studies of their genetic effects on blood pressure, including pharmacogenetic interactions.
Keywords: Alleles; Angiotensinogen; Antihypertensive Agents; Blood Pressure; Female; Genetic Predisposition to Disease; Genotype; Humans; Hypertension; Male; Pharmacogenetics; Polymorphism, Single Nucleotide; Receptors, Adrenergic, beta-1

Association of polymorphisms in the hepatocyte growth factor gene promoter with keratoconus. - Burdon, Kathryn P; Macgregor, Stuart; Bykhovskaya, Yelena; Javadiyan, Sharhbanou; Li, Xiaohui; Laurie, Kate J; Muszynska, Dorota; Lindsay, Richard; Lechner, Judith; Haritunians, Talin; Henders, Anjali K; Dash, Durga; et al. (Invest Ophthalmol Vis Sci, 2011)
PURPOSE: Keratoconus is a progressive disorder of the cornea that can lead to severe visual impairment or blindness. Although several genomic regions have been linked to rare familial forms of keratoconus, no genes have yet been definitively identified for common forms of the disease. METHODS: Two genome-wide association scans were undertaken in parallel. The first used pooled DNA from an Australian cohort, followed by typing of top-ranked single-nucleotide polymorphisms (SNPs) in individual DNA samples. The second was conducted in individually genotyped patients, and controls from the USA. Tag SNPs around the hepatocyte growth factor (HGF) gene were typed in three additional replication cohorts. Serum levels of HGF protein in normal individuals were assessed with ELISA and correlated with genotype. RESULTS: The only SNP observed to be associated in both the pooled discovery and primary replication cohort was rs1014091, located upstream of the HGF gene. The nearby SNP rs3735520 was found to be associated in the individually typed discovery cohort (P = 6.1 × 10(-7)). Genotyping of tag SNPs around HGF revealed association at rs3735520 and rs17501108/rs1014091 in four of the five cohorts. Meta-analysis of all five datasets together yielded suggestive P values for rs3735520 (P = 9.9 × 10(-7)) and rs17501108 (P = 9.9 × 10(-5)). In addition, SNP rs3735520 was found to be associated with serum HGF level in normal individuals (P = 0.036). CONCLUSIONS: Taken together, these results implicate genetic variation at the HGF locus with keratoconus susceptibility.
Keywords: Adult; Aged; Chromosomes, Human, Pair 7; Corneal Topography; Enzyme-Linked Immunosorbent Assay; Genetic Predisposition to Disease; Genome-Wide Association Study; Genotype; Hepatocyte Growth Factor; Humans; Keratoconus; Middle Aged; Nucleic Acid Hybridization; Polymorphism, Single Nucleotide; Promoter Regions, Genetic; Sequence Tagged Sites

Candidate gene association study for diabetic retinopathy in persons with type 2 diabetes: the Candidate gene Association Resource (CARe). - Sobrin, Lucia; Green, Todd; Sim, Xueling; Jensen, Richard A; Tai, E Shyong; Tay, Wan Ting; Wang, Jie Jin; Mitchell, Paul; Sandholm, Niina; Liu, Yiyuan; Hietala, Kustaa; Iyengar, Sudha K; et al. (Invest Ophthalmol Vis Sci, 2011)
PURPOSE: To investigate whether variants in cardiovascular candidate genes, some of which have been previously associated with type 2 diabetes (T2D), diabetic retinopathy (DR), and diabetic nephropathy (DN), are associated with DR in the Candidate gene Association Resource (CARe). METHODS: Persons with T2D who were enrolled in the study (n = 2691) had fundus photography and genotyping of single nucleotide polymorphisms (SNPs) in 2000 candidate genes. Two case definitions were investigated: Early Treatment Diabetic Retinopathy Study (ETDRS) grades ≥ 14 and ≥ 30. The χ² analyses for each CARe cohort were combined by Cochran-Mantel-Haenszel (CMH) pooling of odds ratios (ORs) and corrected for multiple hypothesis testing. Logistic regression was performed with adjustment for other DR risk factors. Results from replication in independent cohorts were analyzed with CMH meta-analysis methods. RESULTS: Among 39 genes previously associated with DR, DN, or T2D, three SNPs in P-selectin (SELP) were associated with DR. The strongest association was to rs6128 (OR = 0.43, P = 0.0001, after Bonferroni correction). These associations remained significant after adjustment for DR risk factors. Among other genes examined, several variants were associated with DR with significant P values, including rs6856425 tagging α-l-iduronidase (IDUA) (P = 2.1 × 10(-5), after Bonferroni correction). However, replication in independent cohorts did not reveal study-wide significant effects. The P values after replication were 0.55 and 0.10 for rs6128 and rs6856425, respectively. CONCLUSIONS: Genes associated with DN, T2D, and vascular diseases do not appear to be consistently associated with DR. A few genetic variants associated with DR, particularly those in SELP and near IDUA, should be investigated in additional DR cohorts.
Keywords: Cardiovascular Diseases; Diabetes Mellitus, Type 2; Diabetic Nephropathies; Diabetic Retinopathy; Genetic Predisposition to Disease; Genome-Wide Association Study; Genotype; Humans; Iduronidase; Odds Ratio; P-Selectin; Polymorphism, Single Nucleotide; Risk Factors

CUBN is a gene locus for albuminuria. - Böger, Carsten A; Chen, Ming-Huei; Tin, Adrienne; Olden, Matthias; Köttgen, Anna; de Boer, Ian H; Fuchsberger, Christian; O'Seaghdha, Conall M; Pattaro, Cristian; Teumer, Alexander; Liu, Ching-Ti; Glazer, Nicole L; et al. (J Am Soc Nephrol, 2011)
Identification of genetic risk factors for albuminuria may alter strategies for early prevention of CKD progression, particularly among patients with diabetes. Little is known about the influence of common genetic variants on albuminuria in both general and diabetic populations. We performed a meta-analysis of data from 63,153 individuals of European ancestry with genotype information from genome-wide association studies (CKDGen Consortium) and from a large candidate gene study (CARe Consortium) to identify susceptibility loci for the quantitative trait urinary albumin-to-creatinine ratio (UACR) and the clinical diagnosis microalbuminuria. We identified an association between a missense variant (I2984V) in the CUBN gene, which encodes cubilin, and both UACR (P = 1.1 × 10(-11)) and microalbuminuria (P = 0.001). We observed similar associations among 6981 African Americans in the CARe Consortium. The associations between this variant and both UACR and microalbuminuria were significant in individuals of European ancestry regardless of diabetes status. Finally, this variant associated with a 41% increased risk for the development of persistent microalbuminuria during 20 years of follow-up among 1304 participants with type 1 diabetes in the prospective DCCT/EDIC Study. In summary, we identified a missense CUBN variant that associates with levels of albuminuria in both the general population and in individuals with diabetes.
Keywords: African Continental Ancestry Group; Albuminuria; European Continental Ancestry Group; Genetic Loci; Genetic Predisposition to Disease; Humans; Mutation, Missense; Receptors, Cell Surface

Depressive symptoms, physical inactivity and risk of cardiovascular mortality in older adults: the Cardiovascular Health Study. - Win, Sithu; Parakh, Kapil; Eze-Nliam, Chete M; Gottdiener, John S; Kop, Willem J; Ziegelstein, Roy C (Heart, 2011)
BACKGROUND: Depressed older individuals have a higher mortality than older persons without depression. Depression is associated with physical inactivity, and low levels of physical activity have been shown in some cohorts to be a partial mediator of the relationship between depression and cardiovascular events and mortality. METHODS: A cohort of 5888 individuals (mean 72.8 ± 5.6 years, 58% female, 16% African-American) from four US communities was followed for an average of 10.3 years. Self-reported depressive symptoms (10-item Center for Epidemiological Studies Depression Scale) were assessed annually and self-reported physical activity was assessed at baseline and at 3 and 7 years. To estimate how much of the increased risk of cardiovascular mortality associated with depressive symptoms was due to physical inactivity, Cox regression with time-varying covariates was used to determine the percentage change in the log HR of depressive symptoms for cardiovascular mortality after adding physical activity variables. RESULTS: At baseline, 20% of participants scored above the cut-off for depressive symptoms. There were 2915 deaths (49.8%), of which 1176 (20.1%) were from cardiovascular causes. Depressive symptoms and physical inactivity each independently increased the risk of cardiovascular mortality and were strongly associated with each other (all p < 0.001). Individuals with both depressive symptoms and physical inactivity had greater cardiovascular mortality than those with either individually (p < 0.001, log rank test). Physical inactivity reduced the log HR of depressive symptoms for cardiovascular mortality by 26% after adjustment. This was similar for persons with (25%) and without (23%) established coronary heart disease. CONCLUSIONS: Physical inactivity accounted for a significant proportion of the risk of cardiovascular mortality due to depressive symptoms in older adults, regardless of coronary heart disease status.
Keywords: Aged; Aged, 80 and over; Cardiovascular Diseases; Depression; Epidemiologic Methods; Female; Humans; Male; Motor Activity; Psychiatric Status Rating Scales; United States

Diabetes mellitus, fasting glucose, and risk of cause-specific death. - Rao Kondapally Seshasai, Sreenivasa; Kaptoge, Stephen; Thompson, Alexander; Di Angelantonio, Emanuele; Gao, Pei; Sarwar, Nadeem; Whincup, Peter H; Mukamal, Kenneth J; Gillum, Richard F; Holme, Ingar; Njølstad, Inger; Fletcher, Astrid; et al. (N Engl J Med, 2011)
BACKGROUND: The extent to which diabetes mellitus or hyperglycemia is related to risk of death from cancer or other nonvascular conditions is uncertain. METHODS: We calculated hazard ratios for cause-specific death, according to baseline diabetes status or fasting glucose level, from individual-participant data on 123,205 deaths among 820,900 people in 97 prospective studies. RESULTS: After adjustment for age, sex, smoking status, and body-mass index, hazard ratios among persons with diabetes as compared with persons without diabetes were as follows: 1.80 (95% confidence interval [CI], 1.71 to 1.90) for death from any cause, 1.25 (95% CI, 1.19 to 1.31) for death from cancer, 2.32 (95% CI, 2.11 to 2.56) for death from vascular causes, and 1.73 (95% CI, 1.62 to 1.85) for death from other causes. Diabetes (vs. no diabetes) was moderately associated with death from cancers of the liver, pancreas, ovary, colorectum, lung, bladder, and breast. Aside from cancer and vascular disease, diabetes (vs. no diabetes) was also associated with death from renal disease, liver disease, pneumonia and other infectious diseases, mental disorders, nonhepatic digestive diseases, external causes, intentional self-harm, nervous-system disorders, and chronic obstructive pulmonary disease. Hazard ratios were appreciably reduced after further adjustment for glycemia measures, but not after adjustment for systolic blood pressure, lipid levels, inflammation or renal markers. Fasting glucose levels exceeding 100 mg per deciliter (5.6 mmol per liter), but not levels of 70 to 100 mg per deciliter (3.9 to 5.6 mmol per liter), were associated with death. A 50-year-old with diabetes died, on average, 6 years earlier than a counterpart without diabetes, with about 40% of the difference in survival attributable to excess nonvascular deaths. CONCLUSIONS: In addition to vascular disease, diabetes is associated with substantial premature death from several cancers, infectious diseases, external causes, intentional self-harm, and degenerative disorders, independent of several major risk factors. (Funded by the British Heart Foundation and others.).
Keywords: Blood Glucose; Cause of Death; Diabetes Mellitus; Female; Humans; Hyperglycemia; Life Expectancy; Male; Middle Aged; Risk; Survival Analysis

Enhanced statistical tests for GWAS in admixed populations: assessment using African Americans from CARe and a Breast Cancer Consortium. - Pasaniuc, Bogdan; Zaitlen, Noah; Lettre, Guillaume; Chen, Gary K; Tandon, Arti; Kao, W H Linda; Ruczinski, Ingo; Fornage, Myriam; Siscovick, David S; Zhu, Xiaofeng; Larkin, Emma; Lange, Leslie A; et al. (PLoS Genet, 2011)
While genome-wide association studies (GWAS) have primarily examined populations of European ancestry, more recent studies often involve additional populations, including admixed populations such as African Americans and Latinos. In admixed populations, linkage disequilibrium (LD) exists both at a fine scale in ancestral populations and at a coarse scale (admixture-LD) due to chromosomal segments of distinct ancestry. Disease association statistics in admixed populations have previously considered SNP association (LD mapping) or admixture association (mapping by admixture-LD), but not both. Here, we introduce a new statistical framework for combining SNP and admixture association in case-control studies, as well as methods for local ancestry-aware imputation. We illustrate the gain in statistical power achieved by these methods by analyzing data of 6,209 unrelated African Americans from the CARe project genotyped on the Affymetrix 6.0 chip, in conjunction with both simulated and real phenotypes, as well as by analyzing the FGFR2 locus using breast cancer GWAS data from 5,761 African-American women. We show that, at typed SNPs, our method yields an 8% increase in statistical power for finding disease risk loci compared to the power achieved by standard methods in case-control studies. At imputed SNPs, we observe an 11% increase in statistical power for mapping disease loci when our local ancestry-aware imputation framework and the new scoring statistic are jointly employed. Finally, we show that our method increases statistical power in regions harboring the causal SNP in the case when the causal SNP is untyped and cannot be imputed. Our methods and our publicly available software are broadly applicable to GWAS in admixed populations.
Keywords: African Americans; Algorithms; Breast Neoplasms; Chromosome Mapping; Coronary Disease; Diabetes Mellitus, Type 2; Female; Gene Frequency; Genetic Variation; Genetics, Population; Genome, Human; Genome-Wide Association Study; Genotype; Humans; Linkage Disequilibrium; Male; Odds Ratio; Phenotype; Polymorphism, Single Nucleotide; Principal Component Analysis; Receptor, Fibroblast Growth Factor, Type 2; Software

Genetic association for renal traits among participants of African ancestry reveals new loci for renal function. - Liu, Ching-Ti; Garnaas, Maija K; Tin, Adrienne; Köttgen, Anna; Franceschini, Nora; Peralta, Carmen A; de Boer, Ian H; Lu, Xiaoning; Atkinson, Elizabeth; Ding, Jingzhong; Nalls, Michael; Shriner, Daniel; et al. (PLoS Genet, 2011)
Chronic kidney disease (CKD) is an increasing global public health concern, particularly among populations of African ancestry. We performed an interrogation of known renal loci, genome-wide association (GWA), and IBC candidate-gene SNP association analyses in African Americans from the CARe Renal Consortium. In up to 8,110 participants, we performed meta-analyses of GWA and IBC array data for estimated glomerular filtration rate (eGFR), CKD (eGFR <60 mL/min/1.73 m(2)), urinary albumin-to-creatinine ratio (UACR), and microalbuminuria (UACR >30 mg/g) and interrogated the 250 kb flanking region around 24 SNPs previously identified in European Ancestry renal GWAS analyses. Findings were replicated in up to 4,358 African Americans. To assess function, individually identified genes were knocked down in zebrafish embryos by morpholino antisense oligonucleotides. Expression of kidney-specific genes was assessed by in situ hybridization, and glomerular filtration was evaluated by dextran clearance. Overall, 23 of 24 previously identified SNPs had direction-consistent associations with eGFR in African Americans, 2 of which achieved nominal significance (UMOD, PIP5K1B). Interrogation of the flanking regions uncovered 24 new index SNPs in African Americans, 12 of which were replicated (UMOD, ANXA9, GCKR, TFDP2, DAB2, VEGFA, ATXN2, GATM, SLC22A2, TMEM60, SLC6A13, and BCAS3). In addition, we identified 3 suggestive loci at DOK6 (p-value = 5.3×10(-7)) and FNDC1 (p-value = 3.0×10(-7)) for UACR, and KCNQ1 with eGFR (p = 3.6×10(-6)). Morpholino knockdown of kcnq1 in the zebrafish resulted in abnormal kidney development and filtration capacity. We identified several SNPs in association with eGFR in African Ancestry individuals, as well as 3 suggestive loci for UACR and eGFR. Functional genetic studies support a role for kcnq1 in glomerular development in zebrafish.
Keywords: Adaptor Proteins, Vesicular Transport; Adult; African Continental Ancestry Group; Aged; Animals; Female; Gene Knockdown Techniques; Genetic Association Studies; Genetic Loci; Genome-Wide Association Study; Glomerular Filtration Rate; Humans; KCNQ1 Potassium Channel; Kidney; Kidney Failure, Chronic; Male; Middle Aged; Neoplasm Proteins; Phenotype; Polymorphism, Single Nucleotide; Zebrafish

Genetic determinants of lipid traits in diverse populations from the population architecture using genomics and epidemiology (PAGE) study. - Dumitrescu, Logan; Carty, Cara L; Taylor, Kira; Schumacher, Fredrick R; Hindorff, Lucia A; Ambite, José L; Anderson, Garnet; Best, Lyle G; Brown-Gentry, Kristin; Bůzková, Petra; Carlson, Christopher S; Cochran, Barbara; et al. (PLoS Genet, 2011)
For the past five years, genome-wide association studies (GWAS) have identified hundreds of common variants associated with human diseases and traits, including high-density lipoprotein cholesterol (HDL-C), low-density lipoprotein cholesterol (LDL-C), and triglyceride (TG) levels. Approximately 95 loci associated with lipid levels have been identified primarily among populations of European ancestry. The Population Architecture using Genomics and Epidemiology (PAGE) study was established in 2008 to characterize GWAS-identified variants in diverse population-based studies. We genotyped 49 GWAS-identified SNPs associated with one or more lipid traits in at least two PAGE studies and across six racial/ethnic groups. We performed a meta-analysis testing for SNP associations with fasting HDL-C, LDL-C, and ln(TG) levels in self-identified European American (~20,000), African American (~9,000), American Indian (~6,000), Mexican American/Hispanic (~2,500), Japanese/East Asian (~690), and Pacific Islander/Native Hawaiian (~175) adults, regardless of lipid-lowering medication use. We replicated 55 of 60 (92%) SNP associations tested in European Americans at p<0.05. Despite sufficient power, we were unable to replicate ABCA1 rs4149268 and rs1883025, CETP rs1864163, and TTC39B rs471364 previously associated with HDL-C and MAFB rs6102059 previously associated with LDL-C. Based on significance (p<0.05) and consistent direction of effect, a majority of replicated genotype-phentoype associations for HDL-C, LDL-C, and ln(TG) in European Americans generalized to African Americans (48%, 61%, and 57%), American Indians (45%, 64%, and 77%), and Mexican Americans/Hispanics (57%, 56%, and 86%). Overall, 16 associations generalized across all three populations. For the associations that did not generalize, differences in effect sizes, allele frequencies, and linkage disequilibrium offer clues to the next generation of association studies for these traits.
Keywords: Adolescent; Adult; Aged; Aged, 80 and over; Continental Population Groups; Female; Gene Frequency; Genetics, Population; Genome-Wide Association Study; Humans; Linkage Disequilibrium; Lipid Metabolism; Lipoproteins, HDL; Lipoproteins, LDL; Male; Middle Aged; Molecular Epidemiology; Polymorphism, Single Nucleotide; Quantitative Trait Loci; Risk Factors; Triglycerides; Young Adult

Genetic loci associated with plasma phospholipid n-3 fatty acids: a meta-analysis of genome-wide association studies from the CHARGE Consortium. - Lemaitre, Rozenn N; Tanaka, Toshiko; Tang, Weihong; Manichaikul, Ani; Foy, Millennia; Kabagambe, Edmond K; Nettleton, Jennifer A; King, Irena B; Weng, Lu-Chen; Bhattacharya, Sayanti; Bandinelli, Stefania; Bis, Joshua C; et al. (PLoS Genet, 2011)
Long-chain n-3 polyunsaturated fatty acids (PUFAs) can derive from diet or from α-linolenic acid (ALA) by elongation and desaturation. We investigated the association of common genetic variation with plasma phospholipid levels of the four major n-3 PUFAs by performing genome-wide association studies in five population-based cohorts comprising 8,866 subjects of European ancestry. Minor alleles of SNPs in FADS1 and FADS2 (desaturases) were associated with higher levels of ALA (p = 3 x 10⁻⁶⁴) and lower levels of eicosapentaenoic acid (EPA, p = 5 x 10⁻⁵⁸) and docosapentaenoic acid (DPA, p = 4 x 10⁻¹⁵⁴). Minor alleles of SNPs in ELOVL2 (elongase) were associated with higher EPA (p = 2 x 10⁻¹²) and DPA (p = 1 x 10⁻⁴³) and lower docosahexaenoic acid (DHA, p = 1 x 10⁻¹⁵). In addition to genes in the n-3 pathway, we identified a novel association of DPA with several SNPs in GCKR (glucokinase regulator, p = 1 x 10⁻⁸). We observed a weaker association between ALA and EPA among carriers of the minor allele of a representative SNP in FADS2 (rs1535), suggesting a lower rate of ALA-to-EPA conversion in these subjects. In samples of African, Chinese, and Hispanic ancestry, associations of n-3 PUFAs were similar with a representative SNP in FADS1 but less consistent with a representative SNP in ELOVL2. Our findings show that common variation in n-3 metabolic pathway genes and in GCKR influences plasma phospholipid levels of n-3 PUFAs in populations of European ancestry and, for FADS1, in other ancestries.
Keywords: Alleles; Continental Population Groups; Fatty Acids, Omega-3; Female; Genetic Loci; Genome-Wide Association Study; Humans; Male; Metabolic Networks and Pathways; Polymorphism, Single Nucleotide

Genetic predictors of fibrin D-dimer levels in healthy adults. - Smith, Nicholas L; Huffman, Jennifer E; Strachan, David P; Huang, Jie; Dehghan, Abbas; Trompet, Stella; Lopez, Lorna M; Shin, So-Youn; Baumert, Jens; Vitart, Veronique; Bis, Joshua C; Wild, Sarah H; et al. (Circulation, 2011)
BACKGROUND: Fibrin fragment D-dimer, one of several peptides produced when crosslinked fibrin is degraded by plasmin, is the most widely used clinical marker of activated blood coagulation. To identity genetic loci influencing D-dimer levels, we performed the first large-scale, genome-wide association search. METHODS AND RESULTS: A genome-wide investigation of the genomic correlates of plasma D-dimer levels was conducted among 21 052 European-ancestry adults. Plasma levels of D-dimer were measured independently in each of 13 cohorts. Each study analyzed the association between ≈2.6 million genotyped and imputed variants across the 22 autosomal chromosomes and natural-log–transformed D-dimer levels using linear regression in additive genetic models adjusted for age and sex. Among all variants, 74 exceeded the genome-wide significance threshold and marked 3 regions. At 1p22, rs12029080 (P=6.4×10(-52)) was 46.0 kb upstream from F3, coagulation factor III (tissue factor). At 1q24, rs6687813 (P=2.4×10(-14)) was 79.7 kb downstream of F5, coagulation factor V. At 4q32, rs13109457 (P=2.9×10(-18)) was located between 2 fibrinogen genes: 10.4 kb downstream from FGG and 3.0 kb upstream from FGA. Variants were associated with a 0.099-, 0.096-, and 0.061-unit difference, respectively, in natural-log–transformed D-dimer and together accounted for 1.8% of the total variance. When adjusted for nonsynonymous substitutions in F5 and FGA loci known to be associated with D-dimer levels, there was no evidence of an additional association at either locus. CONCLUSIONS: Three genes were associated with fibrin D-dimer levels. Of these 3, the F3 association was the strongest, and has not been previously reported.
Keywords: Adult; Aged; Blood Coagulation; European Continental Ancestry Group; Factor V; Female; Fibrin Fibrinogen Degradation Products; Fibrinogen; Genetic Testing; Genome-Wide Association Study; Humans; Male; Middle Aged; Reference Values; Thromboplastin

Genetic variants in novel pathways influence blood pressure and cardiovascular disease risk. - Ehret, Georg B; Munroe, Patricia B; Rice, Kenneth M; Bochud, Murielle; Johnson, Andrew D; Chasman, Daniel I; Smith, Albert V; Tobin, Martin D; Verwoert, Germaine C; Hwang, Shih-Jen; Pihur, Vasyl; Vollenweider, Peter; et al. (Nature, 2011)
Blood pressure is a heritable trait influenced by several biological pathways and responsive to environmental stimuli. Over one billion people worldwide have hypertension (≥140 mm Hg systolic blood pressure or  ≥90 mm Hg diastolic blood pressure). Even small increments in blood pressure are associated with an increased risk of cardiovascular events. This genome-wide association study of systolic and diastolic blood pressure, which used a multi-stage design in 200,000 individuals of European descent, identified sixteen novel loci: six of these loci contain genes previously known or suspected to regulate blood pressure (GUCY1A3-GUCY1B3, NPR3-C5orf23, ADM, FURIN-FES, GOSR2, GNAS-EDN3); the other ten provide new clues to blood pressure physiology. A genetic risk score based on 29 genome-wide significant variants was associated with hypertension, left ventricular wall thickness, stroke and coronary artery disease, but not kidney disease or kidney function. We also observed associations with blood pressure in East Asian, South Asian and African ancestry individuals. Our findings provide new insights into the genetics and biology of blood pressure, and suggest potential novel therapeutic pathways for cardiovascular disease prevention.
Keywords: Africa; Asia; Blood Pressure; Cardiovascular Diseases; Coronary Artery Disease; Europe; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Hypertension; Kidney Diseases; Polymorphism, Single Nucleotide; Stroke

Genetic variants of the NOTCH3 gene in the elderly and magnetic resonance imaging correlates of age-related cerebral small vessel disease. - Schmidt, Helena; Zeginigg, Marion; Wiltgen, Marco; Freudenberger, Paul; Petrovic, Katja; Cavalieri, Margherita; Gider, Pierre; Enzinger, Christian; Fornage, Myriam; Debette, Stephanie; Rotter, Jerome I; Ikram, Mohammad A; et al. (Brain, 2011)
Cerebral small vessel disease-related brain lesions such as white matter lesions and lacunes are common findings of magnetic resonance imaging in the elderly. These lesions are thought to be major contributors to disability in old age, and risk factors that include age and hypertension have been established. The radiological, histopathologic and clinical phenotypes of age-related cerebral small vessel disease remarkably resemble autosomal dominant arteriopathy with subcortical infarcts and leucoencephalopathy, which is caused by mutations in NOTCH3. We hypothesized that genetic variations in NOTCH3 also play a role in age-related cerebral small vessel disease. We directly sequenced all 33 exons, the promoter and 3'-untranslated region of NOTCH3 in 195 participants with either coalescent white matter lesions or lacunes and compared the results to 82 randomly selected participants with no focal changes on magnetic resonance images in the Austrian Stroke Prevention Study. We detected nine common and 33 rare single nucleotide polymorphisms, of which 20 were novel. All common single nucleotide polymorphisms were genotyped in the entire cohort (n = 888), and four of them, rs1043994, rs10404382, rs10423702 and rs1043997, were associated significantly with both the presence and progression of white matter lesions. The association was confined to hypertensives, a result which we replicated in the Cohorts for Heart and Ageing Research in Genomic Epidemiology Consortium on an independent sample of 4773 stroke-free hypertensive elderly individuals of European descent (P = 0.04). The 33 rare single nucleotide polymorphisms were scattered over the NOTCH3 gene with three being located in the promoter region, 24 in exons (18 non-synonymous), three in introns and three in the 3'-untranslated region. None of the single nucleotide polymorphisms affected a cysteine residue. Sorting Intolerant From Tolerant, PolyPhen2 analyses and protein structure simulation consistently predicted six of the non-synonymous single nucleotide polymorphisms (H170R, P496L, V1183M, L1518M, D1823N and V1952M) to be functional, with four being exclusively or mainly detected in subjects with severe white matter lesions. In four individuals with rare non-synonymous single nucleotide polymorphisms, we noted anterior temporal lobe hyperintensity, hyperintensity in the external capsule, lacunar infarcts or subcortical lacunar lesions. None of the observed abnormalities were specific to cerebral autosomal dominant arteriopathy with subcortical infarcts and leucoencephalopathy. This is the first comprehensive study investigating (i) the frequency of NOTCH3 variations in community-dwelling elderly and (ii) their effect on cerebral small vessel disease related magnetic resonance imaging phenotypes. We show that the NOTCH3 gene is highly variable with both common and rare single nucleotide polymorphisms spreading across the gene, and that common variants at the NOTCH3 gene increase the risk of age-related white matter lesions in hypertensives. Additional investigations are required to explore the biological mechanisms underlying the observed association.
Keywords: Aged; Aged, 80 and over; Alleles; Brain; Cerebral Small Vessel Diseases; Exons; Female; Follow-Up Studies; Genetic Association Studies; Genotype; Humans; Hypertension; Magnetic Resonance Imaging; Male; Middle Aged; Phenotype; Promoter Regions, Genetic; Prospective Studies; Receptor, Notch3; Receptors, Notch

Genetic variation near IRS1 associates with reduced adiposity and an impaired metabolic profile. - Kilpeläinen, Tuomas O; Zillikens, M Carola; Stančáková, Alena; Finucane, Francis M; Ried, Janina S; Langenberg, Claudia; Zhang, Weihua; Beckmann, Jacques S; Luan, Jian'an; Vandenput, Liesbeth; Styrkarsdottir, Unnur; Zhou, Yanhua; et al. (Nat Genet, 2011)
Genome-wide association studies have identified 32 loci influencing body mass index, but this measure does not distinguish lean from fat mass. To identify adiposity loci, we meta-analyzed associations between ∼2.5 million SNPs and body fat percentage from 36,626 individuals and followed up the 14 most significant (P < 10(-6)) independent loci in 39,576 individuals. We confirmed a previously established adiposity locus in FTO (P = 3 × 10(-26)) and identified two new loci associated with body fat percentage, one near IRS1 (P = 4 × 10(-11)) and one near SPRY2 (P = 3 × 10(-8)). Both loci contain genes with potential links to adipocyte physiology. Notably, the body-fat-decreasing allele near IRS1 is associated with decreased IRS1 expression and with an impaired metabolic profile, including an increased visceral to subcutaneous fat ratio, insulin resistance, dyslipidemia, risk of diabetes and coronary artery disease and decreased adiponectin levels. Our findings provide new insights into adiposity and insulin resistance.
Keywords: Adiponectin; Adiposity; Alleles; Body Fat Distribution; Body Mass Index; Body Weight; Female; Genetic Variation; Genome-Wide Association Study; Humans; Insulin Receptor Substrate Proteins; Intracellular Signaling Peptides and Proteins; Male; Membrane Proteins; Meta-Analysis as Topic; Metabolome; Obesity; Polymorphism, Single Nucleotide; Subcutaneous Fat

Genome-wide association and large-scale follow up identifies 16 new loci influencing lung function. - Soler Artigas, Maria; Loth, Daan W; Wain, Louise V; Gharib, Sina A; Obeidat, Ma'en; Tang, Wenbo; Zhai, Guangju; Zhao, Jing Hua; Smith, Albert Vernon; Huffman, Jennifer E; Albrecht, Eva; Jackson, Catherine M; et al. (Nat Genet, 2011)
Pulmonary function measures reflect respiratory health and are used in the diagnosis of chronic obstructive pulmonary disease. We tested genome-wide association with forced expiratory volume in 1 second and the ratio of forced expiratory volume in 1 second to forced vital capacity in 48,201 individuals of European ancestry with follow up of the top associations in up to an additional 46,411 individuals. We identified new regions showing association (combined P < 5 × 10(-8)) with pulmonary function in or near MFAP2, TGFB2, HDAC4, RARB, MECOM (also known as EVI1), SPATA9, ARMC2, NCR3, ZKSCAN3, CDC123, C10orf11, LRP1, CCDC38, MMP15, CFDP1 and KCNE2. Identification of these 16 new loci may provide insight into the molecular mechanisms regulating pulmonary function and into molecular targets for future therapy to alleviate reduced lung function.
Keywords: Child; European Continental Ancestry Group; Genome-Wide Association Study; Humans; Pulmonary Disease, Chronic Obstructive; Respiratory Function Tests

Genome-wide association studies of cerebral white matter lesion burden: the CHARGE consortium. - Fornage, Myriam; Debette, Stephanie; Bis, Joshua C; Schmidt, Helena; Ikram, M Arfan; Dufouil, Carole; Sigurdsson, Sigurdur; Lumley, Thomas; DeStefano, Anita L; Fazekas, Franz; Vrooman, Henri A; Shibata, Dean K; et al. (Ann Neurol, 2011)
OBJECTIVE: White matter hyperintensities (WMHs) detectable by magnetic resonance imaging are part of the spectrum of vascular injury associated with aging of the brain and are thought to reflect ischemic damage to the small deep cerebral vessels. WMHs are associated with an increased risk of cognitive and motor dysfunction, dementia, depression, and stroke. Despite a significant heritability, few genetic loci influencing WMH burden have been identified. METHODS: We performed a meta-analysis of genome-wide association studies (GWASs) for WMH burden in 9,361 stroke-free individuals of European descent from 7 community-based cohorts. Significant findings were tested for replication in 3,024 individuals from 2 additional cohorts. RESULTS: We identified 6 novel risk-associated single nucleotide polymorphisms (SNPs) in 1 locus on chromosome 17q25 encompassing 6 known genes including WBP2, TRIM65, TRIM47, MRPL38, FBF1, and ACOX1. The most significant association was for rs3744028 (p(discovery) = 4.0 × 10(-9) ; p(replication) = 1.3 × 10(-7) ; p(combined) = 4.0 × 10(-15) ). Other SNPs in this region also reaching genome-wide significance were rs9894383 (p = 5.3 × 10(-9) ), rs11869977 (p = 5.7 × 10(-9) ), rs936393 (p = 6.8 × 10(-9) ), rs3744017 (p = 7.3 × 10(-9) ), and rs1055129 (p = 4.1 × 10(-8) ). Variant alleles at these loci conferred a small increase in WMH burden (4-8% of the overall mean WMH burden in the sample). INTERPRETATION: This large GWAS of WMH burden in community-based cohorts of individuals of European descent identifies a novel locus on chromosome 17. Further characterization of this locus may provide novel insights into the pathogenesis of cerebral WMH.
Keywords: Aged; Aged, 80 and over; Cerebral Cortex; Chromosomes, Human, Pair 17; Cognition Disorders; Cohort Studies; European Continental Ancestry Group; Female; Gene Frequency; Genetic Predisposition to Disease; Genome-Wide Association Study; Genotype; Humans; Leukoencephalopathies; Magnetic Resonance Imaging; Male; Middle Aged; Movement Disorders; Nerve Fibers, Myelinated; Polymorphism, Single Nucleotide; Residence Characteristics; RNA, Messenger

Genome-wide association study for serum urate concentrations and gout among African Americans identifies genomic risk loci and a novel URAT1 loss-of-function allele. - Tin, Adrienne; Woodward, Owen M; Kao, Wen Hong Linda; Liu, Ching-Ti; Lu, Xiaoning; Nalls, Michael A; Shriner, Daniel; Semmo, Mariam; Akylbekova, Ermeg L; Wyatt, Sharon B; Hwang, Shih-Jen; Yang, Qiong; et al. (Hum Mol Genet, 2011)
Serum urate concentrations are highly heritable and elevated serum urate is a key risk factor for gout. Genome-wide association studies (GWAS) of serum urate in African American (AA) populations are lacking. We conducted a meta-analysis of GWAS of serum urate levels and gout among 5820 AA and a large candidate gene study among 6890 AA and 21 708 participants of European ancestry (EA) within the Candidate Gene Association Resource Consortium. Findings were tested for replication among 1996 independent AA individuals, and evaluated for their association among 28 283 EA participants of the CHARGE Consortium. Functional studies were conducted using (14)C-urate transport assays in mammalian Chinese hamster ovary cells. In the discovery GWAS of serum urate, three loci achieved genome-wide significance (P< 5.0 × 10(-8)): a novel locus near SGK1/SLC2A12 on chromosome 6 (rs9321453, P= 1.0 × 10(-9)), and two loci previously identified in EA participants, SLC2A9 (P= 3.8 × 10(-32)) and SLC22A12 (P= 2.1 × 10(-10)). A novel rare non-synonymous variant of large effect size in SLC22A12, rs12800450 (minor allele frequency 0.01, G65W), was identified and replicated (beta -1.19 mg/dl, P= 2.7 × 10(-16)). (14)C-urate transport assays showed reduced urate transport for the G65W URAT1 mutant. Finally, in analyses of 11 loci previously associated with serum urate in EA individuals, 10 of 11 lead single-nucleotide polymorphisms showed direction-consistent association with urate among AA. In summary, we identified and replicated one novel locus in association with serum urate levels and experimentally characterize the novel G65W variant in URAT1 as a functional allele. Our data support the importance of multi-ethnic GWAS in the identification of novel risk loci as well as functional variants.
Keywords: Adult; African Americans; Aged; Animals; CHO Cells; Cricetinae; European Continental Ancestry Group; Female; Genetic Loci; Genetic Predisposition to Disease; Genome-Wide Association Study; Genotype; Gout; Humans; Loss of Heterozygosity; Male; Middle Aged; Organic Anion Transporters; Organic Cation Transport Proteins; Polymorphism, Single Nucleotide; Uric Acid; Young Adult

A genome-wide association study identifies novel loci associated with circulating IGF-I and IGFBP-3. - Kaplan, Robert C; Petersen, Ann-Kristin; Chen, Ming-Huei; Teumer, Alexander; Glazer, Nicole L; Döring, Angela; Lam, Carolyn S P; Friedrich, Nele; Newman, Anne; Müller, Martina; Yang, Qiong; Homuth, Georg; et al. (Hum Mol Genet, 2011)
Insulin-like growth factor-I (IGF-I) and insulin-like growth factor-binding protein-3 (IGFBP-3) are involved in cell replication, proliferation, differentiation, protein synthesis, carbohydrate homeostasis and bone metabolism. Circulating IGF-I and IGFBP-3 concentrations predict anthropometric traits and risk of cancer and cardiovascular disease. In a genome-wide association study of 10 280 middle-aged and older men and women from four community-based cohort studies, we confirmed a known association of single nucleotide polymorphisms in the IGFBP3 gene region on chromosome 7p12.3 with IGFBP-3 concentrations using a significance threshold of P < 5 × 10(-8) (P = 3.3 × 10(-101)). Furthermore, the same IGFBP3 gene locus (e.g. rs11977526) that was associated with IGFBP-3 concentrations was also associated with the opposite direction of effect, with IGF-I concentration after adjustment for IGFBP-3 concentration (P = 1.9 × 10(-26)). A novel and independent locus on chromosome 7p12.3 (rs700752) had genome-wide significant associations with higher IGFBP-3 (P = 4.4 × 10(-21)) and higher IGF-I (P = 4.9 × 10(-9)) concentrations; when the two measurements were adjusted for one another, the IGF-I association was attenuated but the IGFBP-3 association was not. Two additional loci demonstrated genome-wide significant associations with IGFBP-3 concentration (rs1065656, chromosome 16p13.3, P = 1.2 × 10(-11), IGFALS, a confirmatory finding; and rs4234798, chromosome 4p16.1, P = 4.5 × 10(-10), SORCS2, a novel finding). Together, the four genome-wide significant loci explained 6.5% of the population variation in IGFBP-3 concentration. Furthermore, we observed a borderline statistically significant association between IGF-I concentration and FOXO3 (rs2153960, chromosome 6q21, P = 5.1 × 10(-7)), a locus associated with longevity. These genetic loci deserve further investigation to elucidate the biological basis for the observed associations and clarify their possible role in IGF-mediated regulation of cell growth and metabolism.
Keywords: Aged; Chromosomes, Human, Pair 7; Cohort Studies; European Continental Ancestry Group; Female; Genome-Wide Association Study; Humans; Insulin-Like Growth Factor Binding Protein 3; Insulin-Like Growth Factor I; Male; Polymorphism, Single Nucleotide

Genome-wide association study identifies six new loci influencing pulse pressure and mean arterial pressure. - Wain, Louise V; Verwoert, Germaine C; O'Reilly, Paul F; Shi, Gang; Johnson, Toby; Johnson, Andrew D; Bochud, Murielle; Rice, Kenneth M; Henneman, Peter; Smith, Albert V; Ehret, Georg B; Amin, Najaf; et al. (Nat Genet, 2011)
Numerous genetic loci have been associated with systolic blood pressure (SBP) and diastolic blood pressure (DBP) in Europeans. We now report genome-wide association studies of pulse pressure (PP) and mean arterial pressure (MAP). In discovery (N = 74,064) and follow-up studies (N = 48,607), we identified at genome-wide significance (P = 2.7 × 10(-8) to P = 2.3 × 10(-13)) four new PP loci (at 4q12 near CHIC2, 7q22.3 near PIK3CG, 8q24.12 in NOV and 11q24.3 near ADAMTS8), two new MAP loci (3p21.31 in MAP4 and 10q25.3 near ADRB1) and one locus associated with both of these traits (2q24.3 near FIGN) that has also recently been associated with SBP in east Asians. For three of the new PP loci, the estimated effect for SBP was opposite of that for DBP, in contrast to the majority of common SBP- and DBP-associated variants, which show concordant effects on both traits. These findings suggest new genetic pathways underlying blood pressure variation, some of which may differentially influence SBP and DBP.
Keywords: Arteries; Blood Pressure; Case-Control Studies; Follow-Up Studies; Genetic Loci; Genome-Wide Association Study; Humans; Hypertension; Linkage Disequilibrium; Polymorphism, Single Nucleotide

A genome-wide association study of aging. - Walter, Stefan; Atzmon, Gil; Demerath, Ellen W; Garcia, Melissa E; Kaplan, Robert C; Kumari, Meena; Lunetta, Kathryn L; Milaneschi, Yuri; Tanaka, Toshiko; Tranah, Gregory J; Völker, Uwe; Yu, Lei; et al. (Neurobiol Aging, 2011)
Human longevity and healthy aging show moderate heritability (20%-50%). We conducted a meta-analysis of genome-wide association studies from 9 studies from the Cohorts for Heart and Aging Research in Genomic Epidemiology Consortium for 2 outcomes: (1) all-cause mortality, and (2) survival free of major disease or death. No single nucleotide polymorphism (SNP) was a genome-wide significant predictor of either outcome (p < 5 × 10(-8)). We found 14 independent SNPs that predicted risk of death, and 8 SNPs that predicted event-free survival (p < 10(-5)). These SNPs are in or near genes that are highly expressed in the brain (HECW2, HIP1, BIN2, GRIA1), genes involved in neural development and function (KCNQ4, LMO4, GRIA1, NETO1) and autophagy (ATG4C), and genes that are associated with risk of various diseases including cancer and Alzheimer's disease. In addition to considerable overlap between the traits, pathway and network analysis corroborated these findings. These findings indicate that variation in genes involved in neurological processes may be an important factor in regulating aging free of major disease and achieving longevity.
Keywords: Aging; Genetic Predisposition to Disease; Genome-Wide Association Study; Genotype; Humans; Longevity

Health and function of participants in the Long Life Family Study: A comparison with other cohorts. - Newman, Anne B; Glynn, Nancy W; Taylor, Christopher A; Sebastiani, Paola; Perls, Thomas T; Mayeux, Richard; Christensen, Kaare; Zmuda, Joseph M; Barral, Sandra; Lee, Joseph H; Simonsick, Eleanor M; Walston, Jeremy D; et al. (Aging (Albany NY), 2011)
Individuals from families recruited for the Long Life Family Study (LLFS) (n= 4559) were examined and compared to individuals from other cohorts to determine whether the recruitment targeting longevity resulted in a cohort of individuals with better health and function. Other cohorts with similar data included the Cardiovascular Health Study, the Framingham Heart Study, and the New England Centenarian Study. Diabetes, chronic pulmonary disease and peripheral artery disease tended to be less common in LLFS probands and offspring compared to similar aged persons in the other cohorts. Pulse pressure and triglycerides were lower, high density lipids were higher, and a perceptual speed task and gait speed were better in LLFS. Age-specific comparisons showed differences that would be consistent with a higher peak, later onset of decline or slower rate of change across age in LLFS participants. These findings suggest several priority phenotypes for inclusion in future genetic analysis to identify loci contributing to exceptional survival.
Keywords: Aged; Aged, 80 and over; Aging; Blood Pressure; Cardiovascular Diseases; Cohort Studies; Female; Gait; Humans; Longevity; Male; Middle Aged; Psychomotor Performance; Research Design

Higher serum free testosterone concentration in older women is associated with greater bone mineral density, lean body mass, and total fat mass: the cardiovascular health study. - Rariy, Chevon M; Ratcliffe, Sarah J; Weinstein, Rachel; Bhasin, Shalender; Blackman, Marc R; Cauley, Jane A; Robbins, John; Zmuda, Joseph M; Harris, Tamara B; Cappola, Anne R (J Clin Endocrinol Metab, 2011)
CONTEXT: The physiological importance of endogenous testosterone (T) in older women is poorly understood. OBJECTIVE: The aim of the study was to determine the association of higher total and free T levels with bone mineral density (BMD), lean body mass, and fat mass in elderly women. DESIGN: Total and free T were measured using sensitive assays in 232 community-dwelling women aged 67-94 yr who were enrolled in the Cardiovascular Health Study and had dual-energy x-ray absorptiometry scans. Cross-sectional analyses were performed to examine associations between total and free T and BMD and body composition. RESULTS: In adjusted models, total T was directly associated with BMD at the lumbar spine (P = 0.04) and hip (P = 0.001), but not body composition outcomes, in all women, and after excluding estrogen users and adjusting for estradiol (P = 0.04 and 0.01, respectively). Free T was positively related to hip BMD, lean body mass, and body fat (all P < 0.05), with more than 10% differences in each outcome between women at the highest and lowest ends of the free T range, with attenuation after excluding estrogen users and adjusting for estradiol. CONCLUSIONS: In the setting of the low estradiol levels found in older women, circulating T levels were associated with bone density. Women with higher free T levels had greater lean body mass, consistent with the anabolic effect of T, and, in contrast to men, greater fat mass. Mechanistic studies are required to determine whether a causal relationship exists between T, bone, and body composition in this population and the degree to which any T effects are estrogen-independent.
Keywords: Adipose Tissue; Aged; Aged, 80 and over; Body Mass Index; Bone Density; Cardiovascular Physiological Phenomena; Cohort Studies; Female; Health; Humans; Organ Size; Osmolar Concentration; Osteoporosis, Postmenopausal; Testosterone; Thinness; Up-Regulation

Identification of a sudden cardiac death susceptibility locus at 2q24.2 through genome-wide association in European ancestry individuals. - Arking, Dan E; Junttila, M Juhani; Goyette, Philippe; Huertas-Vazquez, Adriana; Eijgelsheim, Mark; Blom, Marieke T; Newton-Cheh, Christopher; Reinier, Kyndaron; Teodorescu, Carmen; Uy-Evanado, Audrey; Carter-Monroe, Naima; Kaikkonen, Kari S; et al. (PLoS Genet, 2011)
Sudden cardiac death (SCD) continues to be one of the leading causes of mortality worldwide, with an annual incidence estimated at 250,000-300,000 in the United States and with the vast majority occurring in the setting of coronary disease. We performed a genome-wide association meta-analysis in 1,283 SCD cases and >20,000 control individuals of European ancestry from 5 studies, with follow-up genotyping in up to 3,119 SCD cases and 11,146 controls from 11 European ancestry studies, and identify the BAZ2B locus as associated with SCD (P = 1.8×10(-10)). The risk allele, while ancestral, has a frequency of ~1.4%, suggesting strong negative selection and increases risk for SCD by 1.92-fold per allele (95% CI 1.57-2.34). We also tested the role of 49 SNPs previously implicated in modulating electrocardiographic traits (QRS, QT, and RR intervals). Consistent with epidemiological studies showing increased risk of SCD with prolonged QRS/QT intervals, the interval-prolonging alleles are in aggregate associated with increased risk for SCD (P = 0.006).
Keywords: Adult; Aged; Alleles; Chromosomes, Human, Pair 2; Death, Sudden, Cardiac; European Continental Ancestry Group; Female; Genetic Loci; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Male; Middle Aged; Myocardial Contraction; Polymorphism, Single Nucleotide

Large-scale candidate gene analysis in whites and African Americans identifies IL6R polymorphism in relation to atrial fibrillation: the National Heart, Lung, and Blood Institute's Candidate Gene Association Resource (CARe) project. - Schnabel, Renate B; Kerr, Kathleen F; Lubitz, Steven A; Alkylbekova, Ermeg L; Marcus, Gregory M; Sinner, Moritz F; Magnani, Jared W; Wolf, Philip A; Deo, Rajat; Lloyd-Jones, Donald M; Lunetta, Kathryn L; Mehra, Reena; et al. (Circ Cardiovasc Genet, 2011)
BACKGROUND: The genetic background of atrial fibrillation (AF) in whites and African Americans is largely unknown. Genes in cardiovascular pathways have not been systematically investigated. METHODS AND RESULTS: We examined a panel of approximately 50,000 common single-nucleotide polymorphisms (SNPs) in 2095 cardiovascular candidate genes and AF in 3 cohorts with participants of European (n=18,524; 2260 cases) or African American descent (n=3662; 263 cases) in the National Heart, Lung, and Blood Institute's Candidate Gene Association Resource. Results in whites were followed up in the German Competence Network for AF (n=906, 468 cases). The top result was assessed in relation to incident ischemic stroke in the Cohorts for Heart and Aging Research in Genomic Epidemiology Stroke Consortium (n=19,602 whites, 1544 incident strokes). SNP rs4845625 in the IL6R gene was associated with AF (relative risk [RR] C allele, 0.90; 95% confidence interval [CI], 0.85-0.95; P=0.0005) in whites but did not reach statistical significance in African Americans (RR, 0.86; 95% CI, 0.72-1.03; P=0.09). The results were comparable in the German AF Network replication, (RR, 0.71; 95% CI, 0.57-0.89; P=0.003). No association between rs4845625 and stroke was observed in whites. The known chromosome 4 locus near PITX2 in whites also was associated with AF in African Americans (rs4611994; hazard ratio, 1.40; 95% CI, 1.16-1.69; P=0.0005). CONCLUSIONS: In a community-based cohort meta-analysis, we identified genetic association in IL6R with AF in whites. Additionally, we demonstrated that the chromosome 4 locus known from recent genome-wide association studies in whites is associated with AF in African Americans.
Keywords: African Americans; Aged; Alleles; Atrial Fibrillation; Chromosomes, Human, Pair 4; Cohort Studies; European Continental Ancestry Group; Female; Humans; Male; Middle Aged; National Heart, Lung, and Blood Institute (U.S.); Polymorphism, Single Nucleotide; Receptors, Interleukin-6; Risk Factors; Stroke; United States

Lower estimated GFR and higher albuminuria are associated with adverse kidney outcomes. A collaborative meta-analysis of general and high-risk population cohorts. - Gansevoort, Ron T; Matsushita, Kunihiro; van der Velde, Marije; Astor, Brad C; Woodward, Mark; Levey, Andrew S; de Jong, Paul E; Coresh, Josef (Kidney Int, 2011)
Both a low estimated glomerular filtration rate (eGFR) and albuminuria are known risk factors for end-stage renal disease (ESRD). To determine their joint contribution to ESRD and other kidney outcomes, we performed a meta-analysis of nine general population cohorts with 845,125 participants and an additional eight cohorts with 173,892 patients, the latter selected because of their high risk for chronic kidney disease (CKD). In the general population, the risk for ESRD was unrelated to eGFR at values between 75 and 105 ml/min per 1.73 m(2) but increased exponentially at lower levels. Hazard ratios for eGFRs averaging 60, 45, and 15 were 4, 29, and 454, respectively, compared with an eGFR of 95, after adjustment for albuminuria and cardiovascular risk factors. Log albuminuria was linearly associated with log ESRD risk without thresholds. Adjusted hazard ratios at albumin-to-creatinine ratios of 30, 300, and 1000 mg/g were 5, 13, and 28, respectively, compared with an albumin-to-creatinine ratio of 5. Albuminuria and eGFR were associated with ESRD, without evidence for multiplicative interaction. Similar associations were found for acute kidney injury and progressive CKD. In high-risk cohorts, the findings were generally comparable. Thus, lower eGFR and higher albuminuria are risk factors for ESRD, acute kidney injury and progressive CKD in both general and high-risk populations, independent of each other and of cardiovascular risk factors.
Keywords: Aged; Albuminuria; Cohort Studies; Creatinine; Female; Glomerular Filtration Rate; Humans; Kidney Failure, Chronic; Male; Middle Aged; Prognosis; Proportional Hazards Models; Risk Factors

Measurement of organ structure and function enhances understanding of the physiological basis of frailty: the Cardiovascular Health Study. - Sanders, Jason L; Boudreau, Robert M; Fried, Linda P; Walston, Jeremy D; Harris, Tamara B; Newman, Anne B (J Am Geriatr Soc, 2011)
OBJECTIVES: To determine whether disease burden is associated with frailty independent of diagnosed chronic disease and whether physiological measurements provide greater understanding of the etiology of frailty. DESIGN: Cross-sectional. SETTING: Community. PARTICIPANTS: Two thousand four hundred thirty-seven participants in the Cardiovascular Health Study, 1992/93 examination (mean age 74.8 ± 4.8, 43.4% male, 95.8% white). MEASUREMENTS: Disease burden and frailty were tabulated using 10-point scales (0 = healthy, 10 = unhealthy). Disease burden was the sum of measurements characterizing the vasculature, brain, kidneys, lungs, and glucose metabolism. Frailty was assessed using the frailty index reported by Fried. Multivariate linear models were used to determine the association between disease burden (predictor) and frailty (outcome). RESULTS: Unadjusted, 1-point-higher disease burden was associated with a 0.28-point-higher frailty score (P < .001). White matter grade, forced vital capacity, and cystatin-C were particularly strongly and significantly associated with frailty. Disease burden attenuated the association between frailty and age by 29%, and disease burden and age had similar associations with frailty. Disease burden attenuated the association between frailty and fibrinogen, Factor VIII, and C-reactive protein by 32%, 56%, and 83%, respectively. Frailty was associated with diagnosed depression, stroke, cognitive impairment, arthritis, and pulmonary disease but not coronary heart disease, diabetes mellitus, or kidney disease in the presence of a summary of disease burden. In the adjusted model, disease burden remained significantly associated with frailty (β = 0.11, P < .001). CONCLUSION: Disease burden was independently and significantly associated with frailty. These results emphasize that typically unrecognized physiological changes may contribute significantly to frailty.
Keywords: Aged, 80 and over; Cardiovascular Diseases; Chronic Disease; Cost of Illness; Cross-Sectional Studies; Female; Frail Elderly; Humans; Male

Meta-analysis of genome-wide association studies from the CHARGE consortium identifies common variants associated with carotid intima media thickness and plaque. - Bis, Joshua C; Kavousi, Maryam; Franceschini, Nora; Isaacs, Aaron; Abecasis, Goncalo R; Schminke, Ulf; Post, Wendy S; Smith, Albert V; Cupples, L Adrienne; Markus, Hugh S; Schmidt, Reinhold; Huffman, Jennifer E; et al. (Nat Genet, 2011)
Carotid intima media thickness (cIMT) and plaque determined by ultrasonography are established measures of subclinical atherosclerosis that each predicts future cardiovascular disease events. We conducted a meta-analysis of genome-wide association data in 31,211 participants of European ancestry from nine large studies in the setting of the Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) Consortium. We then sought additional evidence to support our findings among 11,273 individuals using data from seven additional studies. In the combined meta-analysis, we identified three genomic regions associated with common carotid intima media thickness and two different regions associated with the presence of carotid plaque (P < 5 × 10(-8)). The associated SNPs mapped in or near genes related to cellular signaling, lipid metabolism and blood pressure homeostasis, and two of the regions were associated with coronary artery disease (P < 0.006) in the Coronary Artery Disease Genome-Wide Replication and Meta-Analysis (CARDIoGRAM) consortium. Our findings may provide new insight into pathways leading to subclinical atherosclerosis and subsequent cardiovascular events.
Keywords: Adult; Aged; Aging; Atherosclerosis; Carotid Intima-Media Thickness; Cohort Studies; Coronary Artery Disease; European Continental Ancestry Group; Genetic Loci; Genetic Predisposition to Disease; Genome, Human; Genome-Wide Association Study; Genotype; Heart; Humans; Middle Aged; Phenotype; Plaque, Atherosclerotic; Polymorphism, Single Nucleotide; Risk Factors

Meta-analysis of genome-wide association studies in >80 000 subjects identifies multiple loci for C-reactive protein levels. - Dehghan, Abbas; Dupuis, Josée; Barbalic, Maja; Bis, Joshua C; Eiriksdottir, Gudny; Lu, Chen; Pellikka, Niina; Wallaschofski, Henri; Kettunen, Johannes; Henneman, Peter; Baumert, Jens; Strachan, David P; et al. (Circulation, 2011)
BACKGROUND: C-reactive protein (CRP) is a heritable marker of chronic inflammation that is strongly associated with cardiovascular disease. We sought to identify genetic variants that are associated with CRP levels. METHODS AND RESULTS: We performed a genome-wide association analysis of CRP in 66 185 participants from 15 population-based studies. We sought replication for the genome-wide significant and suggestive loci in a replication panel comprising 16 540 individuals from 10 independent studies. We found 18 genome-wide significant loci, and we provided evidence of replication for 8 of them. Our results confirm 7 previously known loci and introduce 11 novel loci that are implicated in pathways related to the metabolic syndrome (APOC1, HNF1A, LEPR, GCKR, HNF4A, and PTPN2) or the immune system (CRP, IL6R, NLRP3, IL1F10, and IRF1) or that reside in regions previously not known to play a role in chronic inflammation (PPP1R3B, SALL1, PABPC4, ASCL1, RORA, and BCL7B). We found a significant interaction of body mass index with LEPR (P<2.9×10(-6)). A weighted genetic risk score that was developed to summarize the effect of risk alleles was strongly associated with CRP levels and explained ≈5% of the trait variance; however, there was no evidence for these genetic variants explaining the association of CRP with coronary heart disease. CONCLUSIONS: We identified 18 loci that were associated with CRP levels. Our study highlights immune response and metabolic regulatory pathways involved in the regulation of chronic inflammation.
Keywords: Biomarkers; C-Reactive Protein; Cardiovascular Diseases; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Risk Factors; Vasculitis

New gene functions in megakaryopoiesis and platelet formation. - Gieger, Christian; Radhakrishnan, Aparna; Cvejic, Ana; Tang, Weihong; Porcu, Eleonora; Pistis, Giorgio; Serbanovic-Canic, Jovana; Elling, Ulrich; Goodall, Alison H; Labrune, Yann; Lopez, Lorna M; Mägi, Reedik; et al. (Nature, 2011)
Platelets are the second most abundant cell type in blood and are essential for maintaining haemostasis. Their count and volume are tightly controlled within narrow physiological ranges, but there is only limited understanding of the molecular processes controlling both traits. Here we carried out a high-powered meta-analysis of genome-wide association studies (GWAS) in up to 66,867 individuals of European ancestry, followed by extensive biological and functional assessment. We identified 68 genomic loci reliably associated with platelet count and volume mapping to established and putative novel regulators of megakaryopoiesis and platelet formation. These genes show megakaryocyte-specific gene expression patterns and extensive network connectivity. Using gene silencing in Danio rerio and Drosophila melanogaster, we identified 11 of the genes as novel regulators of blood cell formation. Taken together, our findings advance understanding of novel gene functions controlling fate-determining events during megakaryopoiesis and platelet formation, providing a new example of successful translation of GWAS to function.
Keywords: Animals; Blood Platelets; Cell Size; Drosophila melanogaster; Drosophila Proteins; Europe; Gene Expression Profiling; Gene Silencing; Genome, Human; Genome-Wide Association Study; Hematopoiesis; Humans; Megakaryocytes; Platelet Count; Protein Interaction Maps; Transcription, Genetic; Zebrafish; Zebrafish Proteins

Patterns and predictors of recovery from exhaustion in older adults: the cardiovascular health study. - Whitson, Heather E; Thielke, Stephen; Diehr, Paula; O'Hare, Ann M; Chaves, Paulo H M; Zakai, Neil A; Arnold, Alice; Chaudhry, Sarwat; Ives, Diane; Newman, Anne B (J Am Geriatr Soc, 2011)
OBJECTIVES: To estimate the likelihood of, and factors associated with, recovery from exhaustion in older adults. DESIGN: Secondary analysis of a cohort study. SETTING: Six annual examinations in four U.S. communities. PARTICIPANTS: Four thousand five hundred eighty-four men and women aged 69 and older. MEASUREMENTS: Exhaustion was considered present when a participant responded "a moderate amount" or "most of the time" to either of two questions: "How often have you had a hard time getting going?" and "How often does everything seem an effort?" RESULTS: Of the 964 participants who originally reported exhaustion, 634 (65.8%) were exhaustion free at least once during follow-up. When data from all time points were considered, 48% of those who reported exhaustion were exhaustion free the following year. After adjustment for age, sex, race, education, and marital status, 1-year recovery was less likely in individuals with worse self-rated health and in those who were taking six or more medications or were obese, depressed, or had musculoskeletal pain or history of stroke. In proportional hazards models, the following risk factors were associated with more persistent exhaustion over 5 years: poor self-rated health, six or more medications, obesity, and depression. Recovery was not less likely in participants with a history of cancer or heart disease. CONCLUSION: Exhaustion is common in old age but is dynamic, even in those with a history of cancer and congestive heart failure. Recovery is especially likely in seniors who have a positive perception of their overall health, take few medications, and are not obese or depressed. These findings support the notion that resiliency is associated with physical and psychological well-being.
Keywords: Aged; Aging; Cardiovascular Physiological Phenomena; Exercise Test; Exercise Tolerance; Female; Follow-Up Studies; Geriatric Assessment; Health Status; Humans; Male; Predictive Value of Tests; Recovery of Function; Retrospective Studies; United States

A phenomics-based strategy identifies loci on APOC1, BRAP, and PLCG1 associated with metabolic syndrome phenotype domains. - Avery, Christy L; He, Qianchuan; North, Kari E; Ambite, José L; Boerwinkle, Eric; Fornage, Myriam; Hindorff, Lucia A; Kooperberg, Charles; Meigs, James B; Pankow, James S; Pendergrass, Sarah A; Psaty, Bruce M; et al. (PLoS Genet, 2011)
Despite evidence of the clustering of metabolic syndrome components, current approaches for identifying unifying genetic mechanisms typically evaluate clinical categories that do not provide adequate etiological information. Here, we used data from 19,486 European American and 6,287 African American Candidate Gene Association Resource Consortium participants to identify loci associated with the clustering of metabolic phenotypes. Six phenotype domains (atherogenic dyslipidemia, vascular dysfunction, vascular inflammation, pro-thrombotic state, central obesity, and elevated plasma glucose) encompassing 19 quantitative traits were examined. Principal components analysis was used to reduce the dimension of each domain such that >55% of the trait variance was represented within each domain. We then applied a statistically efficient and computational feasible multivariate approach that related eight principal components from the six domains to 250,000 imputed SNPs using an additive genetic model and including demographic covariates. In European Americans, we identified 606 genome-wide significant SNPs representing 19 loci. Many of these loci were associated with only one trait domain, were consistent with results in African Americans, and overlapped with published findings, for instance central obesity and FTO. However, our approach, which is applicable to any set of interval scale traits that is heritable and exhibits evidence of phenotypic clustering, identified three new loci in or near APOC1, BRAP, and PLCG1, which were associated with multiple phenotype domains. These pleiotropic loci may help characterize metabolic dysregulation and identify targets for intervention.
Keywords: African Americans; Apolipoprotein C-I; Blood Glucose; Dyslipidemias; European Continental Ancestry Group; Genetic Association Studies; Genetic Predisposition to Disease; Genome, Human; Humans; Metabolic Syndrome; Obesity, Abdominal; Phenotype; Phospholipase C gamma; Polymorphism, Single Nucleotide; Quantitative Trait, Heritable; Ubiquitin-Protein Ligases; Vascular Diseases

Separate and combined associations of body-mass index and abdominal adiposity with cardiovascular disease: collaborative analysis of 58 prospective studies. - Wormser, David; Kaptoge, Stephen; Di Angelantonio, Emanuele; Wood, Angela M; Pennells, Lisa; Thompson, Alex; Sarwar, Nadeem; Kizer, Jorge R; Lawlor, Debbie A; Nordestgaard, Børge G; Ridker, Paul; Salomaa, Veikko; et al. (Lancet, 2011)
BACKGROUND: Guidelines differ about the value of assessment of adiposity measures for cardiovascular disease risk prediction when information is available for other risk factors. We studied the separate and combined associations of body-mass index (BMI), waist circumference, and waist-to-hip ratio with risk of first-onset cardiovascular disease. METHODS: We used individual records from 58 cohorts to calculate hazard ratios (HRs) per 1 SD higher baseline values (4.56 kg/m(2) higher BMI, 12.6 cm higher waist circumference, and 0.083 higher waist-to-hip ratio) and measures of risk discrimination and reclassification. Serial adiposity assessments were used to calculate regression dilution ratios. RESULTS: Individual records were available for 221,934 people in 17 countries (14,297 incident cardiovascular disease outcomes; 1.87 million person-years at risk). Serial adiposity assessments were made in up to 63,821 people (mean interval 5.7 years [SD 3.9]). In people with BMI of 20 kg/m(2) or higher, HRs for cardiovascular disease were 1.23 (95% CI 1.17-1.29) with BMI, 1.27 (1.20-1.33) with waist circumference, and 1.25 (1.19-1.31) with waist-to-hip ratio, after adjustment for age, sex, and smoking status. After further adjustment for baseline systolic blood pressure, history of diabetes, and total and HDL cholesterol, corresponding HRs were 1.07 (1.03-1.11) with BMI, 1.10 (1.05-1.14) with waist circumference, and 1.12 (1.08-1.15) with waist-to-hip ratio. Addition of information on BMI, waist circumference, or waist-to-hip ratio to a cardiovascular disease risk prediction model containing conventional risk factors did not importantly improve risk discrimination (C-index changes of -0.0001, -0.0001, and 0.0008, respectively), nor classification of participants to categories of predicted 10-year risk (net reclassification improvement -0.19%, -0.05%, and -0.05%, respectively). Findings were similar when adiposity measures were considered in combination. Reproducibility was greater for BMI (regression dilution ratio 0.95, 95% CI 0.93-0.97) than for waist circumference (0.86, 0.83-0.89) or waist-to-hip ratio (0.63, 0.57-0.70). INTERPRETATION: BMI, waist circumference, and waist-to-hip ratio, whether assessed singly or in combination, do not importantly improve cardiovascular disease risk prediction in people in developed countries when additional information is available for systolic blood pressure, history of diabetes, and lipids. FUNDING: British Heart Foundation and UK Medical Research Council.
Keywords: Age Factors; Blood Pressure; Body Mass Index; Cardiovascular Diseases; Cholesterol; Cholesterol, HDL; Diabetes Mellitus; Female; Humans; Male; Middle Aged; Obesity, Abdominal; Proportional Hazards Models; Prospective Studies; Risk Assessment; Sex Factors; Smoking; Systole; Waist Circumference; Waist-Hip Ratio

Subclinical vascular disease burden and risk for death and cardiovascular events in older community dwellers. - Inzitari, Marco; Arnold, Alice M; Patel, Kushang V; Mercer, Laina D; Karlamangla, Arun; Ding, Jingzhong; Psaty, Bruce M; Williamson, Jeff D; Kuller, Lewis H; Newman, Anne B (J Gerontol A Biol Sci Med Sci, 2011)
BACKGROUND: Individual measures and previous composite measures of subclinical vascular disease defined high risk for cardiovascular events, but did not detect low and modest risk. A different approach might better describe the spectrum from low to high risk. Methods and Results. In the Cardiovascular Health Study, 3,252 participants without history of clinical cardiovascular disease (M ± SD 74.3 years ± 5.1, 63% women, 17% African Americans) had noninvasive vascular assessments in 1992-1993. We assigned a score of 0, 1, or 2 (no, mild, or severe abnormalities) to ankle-arm index, electrocardiogram, and common carotid intima-media thickness, based on clinical cutoffs. A summary index (range 0-6, absent to severe disease) summed individual scores. Abdominal aortic ultrasound and brain magnetic resonance imaging were collected in a subsample. Mortality and incident cardiovascular events were identified through June 2008. Event and death rates increased across index grades. Comparing grades 1 to 5+ with absent disease, and adjusting for demographics, hazard ratios for cardiovascular events within 8 years ranged from 1.1 (95% confidence interval 0.8-1.6) to 4.7 (3.4-6.9) and, for mortality, from 1.5 (1.0-2.3) to 5.0 (3.3-7.7) (p for trend across grades <.001 for both outcomes). Adjustment for cardiovascular risk factors did not substantially change the associations. The index improved mortality risk classification over demographics and risk factors in participants who did not die during the follow-up. Including in the index the aortic ultrasound and the brain magnetic resonance imaging further improved risk classification. CONCLUSIONS: Older adults with minimal subclinical vascular disease had low cardiovascular events risk and mortality. This approach might more fully account for vascular burden.
Keywords: Aged; Aged, 80 and over; Cardiovascular Diseases; Cost of Illness; Female; Humans; Male; Risk; Vascular Diseases

Total zinc intake may modify the glucose-raising effect of a zinc transporter (SLC30A8) variant: a 14-cohort meta-analysis. - Kanoni, Stavroula; Nettleton, Jennifer A; Hivert, Marie-France; Ye, Zheng; van Rooij, Frank J A; Shungin, Dmitry; Sonestedt, Emily; Ngwa, Julius S; Wojczynski, Mary K; Lemaitre, Rozenn N; Gustafsson, Stefan; Anderson, Jennifer S; et al. (Diabetes, 2011)
OBJECTIVE: Many genetic variants have been associated with glucose homeostasis and type 2 diabetes in genome-wide association studies. Zinc is an essential micronutrient that is important for β-cell function and glucose homeostasis. We tested the hypothesis that zinc intake could influence the glucose-raising effect of specific variants. RESEARCH DESIGN AND METHODS: We conducted a 14-cohort meta-analysis to assess the interaction of 20 genetic variants known to be related to glycemic traits and zinc metabolism with dietary zinc intake (food sources) and a 5-cohort meta-analysis to assess the interaction with total zinc intake (food sources and supplements) on fasting glucose levels among individuals of European ancestry without diabetes. RESULTS: We observed a significant association of total zinc intake with lower fasting glucose levels (β-coefficient ± SE per 1 mg/day of zinc intake: -0.0012 ± 0.0003 mmol/L, summary P value = 0.0003), while the association of dietary zinc intake was not significant. We identified a nominally significant interaction between total zinc intake and the SLC30A8 rs11558471 variant on fasting glucose levels (β-coefficient ± SE per A allele for 1 mg/day of greater total zinc intake: -0.0017 ± 0.0006 mmol/L, summary interaction P value = 0.005); this result suggests a stronger inverse association between total zinc intake and fasting glucose in individuals carrying the glucose-raising A allele compared with individuals who do not carry it. None of the other interaction tests were statistically significant. CONCLUSIONS: Our results suggest that higher total zinc intake may attenuate the glucose-raising effect of the rs11558471 SLC30A8 (zinc transporter) variant. Our findings also support evidence for the association of higher total zinc intake with lower fasting glucose levels.
Keywords: Blood Glucose; Cation Transport Proteins; Cohort Studies; Humans; Polymorphism, Single Nucleotide; Zinc; Zinc Transporter 8

Trajectory of cognitive decline as a predictor of psychosis in early Alzheimer disease in the cardiovascular health study. - Emanuel, James E; Lopez, Oscar L; Houck, Patricia R; Becker, James T; Weamer, Elise A; Demichele-Sweet, Mary Ann A; Kuller, Lewis; Sweet, Robert A (Am J Geriatr Psychiatry, 2011)
OBJECTIVE: To compare the trajectories of cognitive decline between groups with, and without, the later development of psychotic symptoms during Alzheimer disease (AD) or mild cognitive impairment (MCI). DESIGN: : The authors examined cognitive function in a new analysis of an existing data set, the Cardiovascular Health Study, an epidemiologic, longitudinal follow-up study. Our analyses examined 9 years of follow-up data. SETTING: Community. PARTICIPANTS: The authors examined subjects who were without dementia at study entry, received a diagnosis of AD or MCI during follow-up, and had been rated on the Neuropsychiatric Inventory for the presence of psychosis; 362 participants for the modified Mini-Mental State Examination (3MS) analysis and 350 participants for the digit symbol substitution test (DSST) analysis had sufficient follow-up data and apolipoprotein-∊ (APOE) genotyping. MEASUREMENTS: The 3MS and DSST were administered annually and analyzed using mixed-effects models including APOE4 status. RESULTS: : Mean 3MS and DSST scores did not differ between AD with psychosis (AD + P) and without psychosis groups at baseline. The 3MS and DSST scores decreased more rapidly in subjects who ultimately developed psychosis. CONCLUSIONS: Individuals who ultimately develop psychosis have more rapid cognitive deterioration during the earliest phases of AD than individuals with AD not developing psychosis. The genetic and other neurobiologic factors leading to the expression of AD + P may exert their effects by acceleration of the neurodegenerative process.
Keywords: Aged; Alzheimer Disease; Chi-Square Distribution; Female; Follow-Up Studies; Humans; Longitudinal Studies; Male; Neuropsychological Tests; Psychiatric Status Rating Scales; Psychotic Disorders; Time Factors

Age and association of kidney measures with mortality and end-stage renal disease. - Hallan, Stein I; Matsushita, Kunihiro; Sang, Yingying; Mahmoodi, Bakhtawar K; Black, Corri; Ishani, Areef; Kleefstra, Nanne; Naimark, David; Roderick, Paul; Tonelli, Marcello; Wetzels, Jack F M; Astor, Brad C; et al. (JAMA, 2012)
CONTEXT: Chronic kidney disease (CKD) is prevalent in older individuals, but the risk implications of low estimated glomerular filtration rate (eGFR) and high albuminuria across the full age range are controversial. OBJECTIVE: To evaluate possible effect modification (interaction) by age of the association of eGFR and albuminuria with clinical risk, examining both relative and absolute risks. DESIGN, SETTING, AND PARTICIPANTS: Individual-level meta-analysis including 2,051,244 participants from 33 general population or high-risk (of vascular disease) cohorts and 13 CKD cohorts from Asia, Australasia, Europe, and North/South America, conducted in 1972-2011 with a mean follow-up time of 5.8 years (range, 0-31 years). MAIN OUTCOME MEASURES: Hazard ratios (HRs) of mortality and end-stage renal disease (ESRD) according to eGFR and albuminuria were meta-analyzed across age categories after adjusting for sex, race, cardiovascular disease, diabetes, systolic blood pressure, cholesterol, body mass index, and smoking. Absolute risks were estimated using HRs and average incidence rates. RESULTS: Mortality (112,325 deaths) and ESRD (8411 events) risks were higher at lower eGFR and higher albuminuria in every age category. In general and high-risk cohorts, relative mortality risk for reduced eGFR decreased with increasing age; eg, adjusted HRs at an eGFR of 45 mL/min/1.73 m2 vs 80 mL/min/1.73 m2 were 3.50 (95% CI, 2.55-4.81), 2.21 (95% CI, 2.02-2.41), 1.59 (95% CI, 1.42-1.77), and 1.35 (95% CI, 1.23-1.48) in age categories 18-54, 55-64, 65-74, and ≥75 years, respectively (P <.05 for age interaction). Absolute risk differences for the same comparisons were higher at older age (9.0 [95% CI, 6.0-12.8], 12.2 [95% CI, 10.3-14.3], 13.3 [95% CI, 9.0-18.6], and 27.2 [95% CI, 13.5-45.5] excess deaths per 1000 person-years, respectively). For increased albuminuria, reduction of relative risk with increasing age was less evident, while differences in absolute risk were higher in older age categories (7.5 [95% CI, 4.3-11.9], 12.2 [95% CI, 7.9-17.6], 22.7 [95% CI, 15.3-31.6], and 34.3 [95% CI, 19.5-52.4] excess deaths per 1000 person-years, respectively by age category, at an albumin-creatinine ratio of 300 mg/g vs 10 mg/g). In CKD cohorts, adjusted relative hazards of mortality did not decrease with age. In all cohorts, ESRD relative risks and absolute risk differences at lower eGFR or higher albuminuria were comparable across age categories. CONCLUSIONS: Both low eGFR and high albuminuria were independently associated with mortality and ESRD regardless of age across a wide range of populations. Mortality showed lower relative risk but higher absolute risk differences at older age.
Keywords: Adolescent; Adult; Age Factors; Aged; Albuminuria; Cohort Studies; Female; Glomerular Filtration Rate; Humans; Kidney; Kidney Failure, Chronic; Male; Middle Aged; Risk; Young Adult

Association between chromosome 9p21 variants and the ankle-brachial index identified by a meta-analysis of 21 genome-wide association studies. - Murabito, Joanne M; White, Charles C; Kavousi, Maryam; Sun, Yan V; Feitosa, Mary F; Nambi, Vijay; Lamina, Claudia; Schillert, Arne; Coassin, Stefan; Bis, Joshua C; Broer, Linda; Crawford, Dana C; et al. (Circ Cardiovasc Genet, 2012)
BACKGROUND: Genetic determinants of peripheral arterial disease (PAD) remain largely unknown. To identify genetic variants associated with the ankle-brachial index (ABI), a noninvasive measure of PAD, we conducted a meta-analysis of genome-wide association study data from 21 population-based cohorts. METHODS AND RESULTS: Continuous ABI and PAD (ABI ≤0.9) phenotypes adjusted for age and sex were examined. Each study conducted genotyping and imputed data to the ≈2.5 million single nucleotide polymorphisms (SNPs) in HapMap. Linear and logistic regression models were used to test each SNP for association with ABI and PAD using additive genetic models. Study-specific data were combined using fixed effects inverse variance weighted meta-analyses. There were a total of 41 692 participants of European ancestry (≈60% women, mean ABI 1.02 to 1.19), including 3409 participants with PAD and with genome-wide association study data available. In the discovery meta-analysis, rs10757269 on chromosome 9 near CDKN2B had the strongest association with ABI (β=-0.006, P=2.46×10(-8)). We sought replication of the 6 strongest SNP associations in 5 population-based studies and 3 clinical samples (n=16 717). The association for rs10757269 strengthened in the combined discovery and replication analysis (P=2.65×10(-9)). No other SNP associations for ABI or PAD achieved genome-wide significance. However, 2 previously reported candidate genes for PAD and 1 SNP associated with coronary artery disease were associated with ABI: DAB21P (rs13290547, P=3.6×10(-5)), CYBA (rs3794624, P=6.3×10(-5)), and rs1122608 (LDLR, P=0.0026). CONCLUSIONS: Genome-wide association studies in more than 40 000 individuals identified 1 genome wide significant association on chromosome 9p21 with ABI. Two candidate genes for PAD and 1 SNP for coronary artery disease are associated with ABI.
Keywords: Adult; Age Factors; Aged; Aged, 80 and over; Alleles; Ankle Brachial Index; Chromosomes, Human, Pair 9; Cohort Studies; Cyclin-Dependent Kinase Inhibitor p15; Female; Genome-Wide Association Study; Genotype; HapMap Project; Humans; Logistic Models; Male; Middle Aged; Peripheral Vascular Diseases; Phenotype; Polymorphism, Single Nucleotide; Risk Factors; Sex Factors

The association between waist circumference and risk of mortality considering body mass index in 65- to 74-year-olds: a meta-analysis of 29 cohorts involving more than 58 000 elderly persons. - de Hollander, Ellen L; Bemelmans, Wanda Je; Boshuizen, Hendriek C; Friedrich, Nele; Wallaschofski, Henri; Guallar-Castillón, Pilar; Walter, Stefan; Zillikens, M Carola; Rosengren, Annika; Lissner, Lauren; Bassett, Julie K; Giles, Graham G; et al. (Int J Epidemiol, 2012)
BACKGROUND: For the elderly, the association between waist circumference (WC) and mortality considering body mass index (BMI) remains unclear, and thereby also the evidence base for using these anthropometric measures in clinical practice. This meta-analysis examined the association between WC categories and (cause-specific) mortality within BMI categories. Furthermore, the association of continuous WC with lowest and increased mortality risks was examined. METHODS: Age- and smoking-adjusted relative risks (RRs) of mortality associated with WC-BMI categories and continuous WC (including WC and WC(2)) were calculated by the investigators and pooled by means of random-effects models. RESULTS: During a 5-year-follow-up of 32 678 men and 25 931 women, we ascertained 3318 and 1480 deaths, respectively. A large WC (men: ≥102 cm, women: ≥88 cm) was associated with increased all-cause mortality RRs for those in the 'healthy' weight {1.7 [95% confidence interval (CI): 1.2-2.2], 1.7 (95% CI: 1.3-2.3)}, overweight [1.1(95% CI: 1.0-1.3), 1.4 (95%: 1.1-1.7)] and obese [1.1 (95% CI: 1.0-1.3), 1.6 (95% CI: 1.3-1.9)] BMI category compared with the 'healthy' weight (20-24.9 kg/m(2)) and a small WC (<94 cm, men; <80 cm, women) category. Underweight was associated with highest all-cause mortality RRs in men [2.2 (95% CI: 1.8-2.8)] and women [2.3 (95% CI: 1.8-3.1]. We found a J-shaped association for continuous WC with all-cause, cardiovascular (CVD) and cancer, and a U-shaped association with respiratory disease mortality (P < 0.05). An all-cause (CVD) mortality RR of 2.0 was associated with a WC of 132 cm (123 cm) in men and 116 cm (105 cm) in women. CONCLUSIONS: Our results showed increased mortality risks for elderly people with an increased WC-even across BMI categories- and for those who were classified as 'underweight' using BMI. The results provide a solid basis for re-evaluation of WC cut-points in ageing populations.
Keywords: Aged; Body Mass Index; Body Weight; Cardiovascular Diseases; Female; Humans; Male; Mortality; Neoplasms; Overweight; Respiratory Tract Diseases; Risk Assessment; Waist Circumference

Association of genetic loci with sleep apnea in European Americans and African-Americans: the Candidate Gene Association Resource (CARe). - Patel, Sanjay R; Goodloe, Robert; De, Gourab; Kowgier, Matthew; Weng, Jia; Buxbaum, Sarah G; Cade, Brian; Fulop, Tibor; Gharib, Sina A; Gottlieb, Daniel J; Hillman, David; Larkin, Emma K; et al. (PLoS One, 2012)
Although obstructive sleep apnea (OSA) is known to have a strong familial basis, no genetic polymorphisms influencing apnea risk have been identified in cross-cohort analyses. We utilized the National Heart, Lung, and Blood Institute (NHLBI) Candidate Gene Association Resource (CARe) to identify sleep apnea susceptibility loci. Using a panel of 46,449 polymorphisms from roughly 2,100 candidate genes on a customized Illumina iSelect chip, we tested for association with the apnea hypopnea index (AHI) as well as moderate to severe OSA (AHI≥15) in 3,551 participants of the Cleveland Family Study and two cohorts participating in the Sleep Heart Health Study.Among 647 African-Americans, rs11126184 in the pleckstrin (PLEK) gene was associated with OSA while rs7030789 in the lysophosphatidic acid receptor 1 (LPAR1) gene was associated with AHI using a chip-wide significance threshold of p-value<2×10(-6). Among 2,904 individuals of European ancestry, rs1409986 in the prostaglandin E2 receptor (PTGER3) gene was significantly associated with OSA. Consistency of effects between rs7030789 and rs1409986 in LPAR1 and PTGER3 and apnea phenotypes were observed in independent clinic-based cohorts.Novel genetic loci for apnea phenotypes were identified through the use of customized gene chips and meta-analyses of cohort data with replication in clinic-based samples. The identified SNPs all lie in genes associated with inflammation suggesting inflammation may play a role in OSA pathogenesis.
Keywords: Adult; African Americans; Aged; Alleles; European Continental Ancestry Group; Female; Genetic Association Studies; Genetic Loci; Genetic Predisposition to Disease; Genotype; Humans; Male; Middle Aged; Phenotype; Polymorphism, Single Nucleotide; Polysomnography; Sleep Apnea, Obstructive

Associations of kidney disease measures with mortality and end-stage renal disease in individuals with and without diabetes: a meta-analysis. - Fox, Caroline S; Matsushita, Kunihiro; Woodward, Mark; Bilo, Henk J G; Chalmers, John; Heerspink, Hiddo J Lambers; Lee, Brian J; Perkins, Robert M; Rossing, Peter; Sairenchi, Toshimi; Tonelli, Marcello; Vassalotti, Joseph A; et al. (Lancet, 2012)
BACKGROUND: Chronic kidney disease is characterised by low estimated glomerular filtration rate (eGFR) and high albuminuria, and is associated with adverse outcomes. Whether these risks are modified by diabetes is unknown. METHODS: We did a meta-analysis of studies selected according to Chronic Kidney Disease Prognosis Consortium criteria. Data transfer and analyses were done between March, 2011, and June, 2012. We used Cox proportional hazards models to estimate the hazard ratios (HR) of mortality and end-stage renal disease (ESRD) associated with eGFR and albuminuria in individuals with and without diabetes. FINDINGS: We analysed data for 1,024,977 participants (128,505 with diabetes) from 30 general population and high-risk cardiovascular cohorts and 13 chronic kidney disease cohorts. In the combined general population and high-risk cohorts with data for all-cause mortality, 75,306 deaths occurred during a mean follow-up of 8·5 years (SD 5·0). In the 23 studies with data for cardiovascular mortality, 21,237 deaths occurred from cardiovascular disease during a mean follow-up of 9·2 years (SD 4·9). In the general and high-risk cohorts, mortality risks were 1·2-1·9 times higher for participants with diabetes than for those without diabetes across the ranges of eGFR and albumin-to-creatinine ratio (ACR). With fixed eGFR and ACR reference points in the diabetes and no diabetes groups, HR of mortality outcomes according to lower eGFR and higher ACR were much the same in participants with and without diabetes (eg, for all-cause mortality at eGFR 45 mL/min per 1·73 m(2) [vs 95 mL/min per 1·73 m(2)], HR 1·35; 95% CI 1·18-1·55; vs 1·33; 1·19-1·48 and at ACR 30 mg/g [vs 5 mg/g], 1·50; 1·35-1·65 vs 1·52; 1·38-1·67). The overall interactions were not significant. We identified much the same findings for ESRD in the chronic kidney disease cohorts. INTERPRETATION: Despite higher risks for mortality and ESRD in diabetes, the relative risks of these outcomes by eGFR and ACR are much the same irrespective of the presence or absence of diabetes, emphasising the importance of kidney disease as a predictor of clinical outcomes. FUNDING: US National Kidney Foundation.
Keywords: Aged; Albuminuria; Cardiovascular Diseases; Cause of Death; Diabetic Nephropathies; Female; Glomerular Filtration Rate; Humans; Kidney Failure, Chronic; Male; Middle Aged; Risk Factors

Classification algorithms for predicting sleepiness and sleep apnea severity. - Eiseman, Nathaniel A; Westover, M Brandon; Mietus, Joseph E; Thomas, Robert J; Bianchi, Matt T (J Sleep Res, 2012)
Identifying predictors of subjective sleepiness and severity of sleep apnea are important yet challenging goals in sleep medicine. Classification algorithms may provide insights, especially when large data sets are available. We analyzed polysomnography and clinical features available from the Sleep Heart Health Study. The Epworth Sleepiness Scale and the apnea-hypopnea index were the targets of three classifiers: k-nearest neighbor, naive Bayes and support vector machine algorithms. Classification was based on up to 26 features including demographics, polysomnogram, and electrocardiogram (spectrogram). Naive Bayes was best for predicting abnormal Epworth class (0-10 versus 11-24), although prediction was weak: polysomnogram features had 16.7% sensitivity and 88.8% specificity; spectrogram features had 5.3% sensitivity and 96.5% specificity. The support vector machine performed similarly to naive Bayes for predicting sleep apnea class (0-5 versus >5): 59.0% sensitivity and 74.5% specificity using clinical features and 43.4% sensitivity and 83.5% specificity using spectrographic features compared with the naive Bayes classifier, which had 57.5% sensitivity and 73.7% specificity (clinical), and 39.0% sensitivity and 82.7% specificity (spectrogram). Mutual information analysis confirmed the minimal dependency of the Epworth score on any feature, while the apnea-hypopnea index showed modest dependency on body mass index, arousal index, oxygenation and spectrogram features. Apnea classification was modestly accurate, using either clinical or spectrogram features, and showed lower sensitivity and higher specificity than common sleep apnea screening tools. Thus, clinical prediction of sleep apnea may be feasible with easily obtained demographic and electrocardiographic analysis, but the utility of the Epworth is questioned by its minimal relation to clinical, electrocardiographic, or polysomnographic features.
Keywords: Adult; Algorithms; Disorders of Excessive Somnolence; Electrocardiography; Humans; Polysomnography; Prognosis; Psychometrics; Sensitivity and Specificity; Severity of Illness Index; Sleep Apnea, Obstructive; Sleep Stages

Common folate gene variant, MTHFR C677T, is associated with brain structure in two independent cohorts of people with mild cognitive impairment. - Rajagopalan, Priya; Jahanshad, Neda; Stein, Jason L; Hua, Xue; Madsen, Sarah K; Kohannim, Omid; Hibar, Derrek P; Toga, Arthur W; Jack, Clifford R; Saykin, Andrew J; Green, Robert C; Weiner, Michael W; et al. (Neuroimage Clin, 2012)
A commonly carried C677T polymorphism in a folate-related gene, MTHFR, is associated with higher plasma homocysteine, a well-known mediator of neuronal damage and brain atrophy. As homocysteine promotes brain atrophy, we set out to discover whether people carrying the C677T MTHFR polymorphism which increases homocysteine, might also show systematic differences in brain structure. Using tensor-based morphometry, we tested this association in 359 elderly Caucasian subjects with mild cognitive impairment (MCI) (mean age: 75 ± 7.1 years) scanned with brain MRI and genotyped as part of Alzheimer's Disease Neuroimaging Initiative. We carried out a replication study in an independent, non-overlapping sample of 51 elderly Caucasian subjects with MCI (mean age: 76 ± 5.5 years), scanned with brain MRI and genotyped for MTHFR, as part of the Cardiovascular Health Study. At each voxel in the brain, we tested to see where regional volume differences were associated with carrying one or more MTHFR 'T' alleles. In ADNI subjects, carriers of the MTHFR risk allele had detectable brain volume deficits, in the white matter, of up to 2-8% per risk T allele locally at baseline and showed accelerated brain atrophy of 0.5-1.5% per T allele at 1 year follow-up, after adjusting for age and sex. We replicated these brain volume deficits of up to 5-12% per MTHFR T allele in the independent cohort of CHS subjects. As expected, the associations weakened after controlling for homocysteine levels, which the risk gene affects. The MTHFR risk variant may thus promote brain atrophy by elevating homocysteine levels. This study aims to investigate the spatially detailed effects of this MTHFR polymorphism on brain structure in 3D, pointing to a causal pathway that may promote homocysteine-mediated brain atrophy in elderly people with MCI.

Common genetic variants differentially influence the transition from clinically defined states of fasting glucose metabolism. - Walford, G A; Green, T; Neale, B; Isakova, T; Rotter, J I; Grant, S F A; Fox, C S; Pankow, J S; Wilson, J G; Meigs, J B; Siscovick, D S; Bowden, D W; et al. (Diabetologia, 2012)
AIMS/HYPOTHESIS: Common genetic variants have been associated with type 2 diabetes. We hypothesised that a subset of these variants may have different effects on the transition from normal fasting glucose (NFG) to impaired fasting glucose (IFG) than on that from IFG to diabetes. METHODS: We identified 16 type 2 diabetes risk variants from the Illumina Broad Candidate-gene Association Resource (CARe) array genotyped in 26,576 CARe participants. Participants were categorised at baseline as NFG, IFG or type 2 diabetic (n = 16,465, 8,017 or 2,291, respectively). Using Cox proportional hazards and likelihood ratio tests (LRTs), we compared rates of progression by genotype for 4,909 (NFG to IFG) and 1,518 (IFG to type 2 diabetes) individuals, respectively. We then performed multinomial regression analyses at baseline, comparing the risk of assignment to the NFG, IFG or diabetes groups by genotype. RESULTS: The rate of progression from NFG to IFG was significantly greater in participants carrying the risk allele at MTNR1B (p = 1 × 10(-4)), nominally greater at GCK and SLC30A8 (p < 0.05) and nominally smaller at IGF2BP2 (p = 0.01) than the rate of progression from IFG to diabetes by the LRT. Results of the baseline, multinomial regression model were consistent with these findings. CONCLUSIONS/INTERPRETATION: Common genetic risk variants at GCK, SLC30A8, IGF2BP2 and MTNR1B influence to different extents the development of IFG and the transition from IFG to type 2 diabetes. Our findings may have implications for understanding the genetic contribution of these variants to the development of IFG and type 2 diabetes.
Keywords: Adult; Aged; Blood Glucose; Cohort Studies; Diabetes Mellitus, Type 2; Disease Progression; Fasting; Female; Genetic Variation; Genotype; Humans; Male; Middle Aged; Models, Genetic; Polymorphism, Single Nucleotide; Proportional Hazards Models; Regression Analysis; Risk

Comparison of risk prediction using the CKD-EPI equation and the MDRD study equation for estimated glomerular filtration rate. - Matsushita, Kunihiro; Mahmoodi, Bakhtawar K; Woodward, Mark; Emberson, Jonathan R; Jafar, Tazeen H; Jee, Sun Ha; Polkinghorne, Kevan R; Shankar, Anoop; Smith, David H; Tonelli, Marcello; Warnock, David G; Wen, Chi-Pang; et al. (JAMA, 2012)
CONTEXT: The Chronic Kidney Disease Epidemiology Collaboration (CKD-EPI) equation more accurately estimates glomerular filtration rate (GFR) than the Modification of Diet in Renal Disease (MDRD) Study equation using the same variables, especially at higher GFR, but definitive evidence of its risk implications in diverse settings is lacking. OBJECTIVE: To evaluate risk implications of estimated GFR using the CKD-EPI equation compared with the MDRD Study equation in populations with a broad range of demographic and clinical characteristics. DESIGN, SETTING, AND PARTICIPANTS: A meta-analysis of data from 1.1 million adults (aged ≥ 18 years) from 25 general population cohorts, 7 high-risk cohorts (of vascular disease), and 13 CKD cohorts. Data transfer and analyses were conducted between March 2011 and March 2012. MAIN OUTCOME MEASURES: All-cause mortality (84,482 deaths from 40 cohorts), cardiovascular mortality (22,176 events from 28 cohorts), and end-stage renal disease (ESRD) (7644 events from 21 cohorts) during 9.4 million person-years of follow-up; the median of mean follow-up time across cohorts was 7.4 years (interquartile range, 4.2-10.5 years). RESULTS: Estimated GFR was classified into 6 categories (≥90, 60-89, 45-59, 30-44, 15-29, and <15 mL/min/1.73 m(2)) by both equations. Compared with the MDRD Study equation, 24.4% and 0.6% of participants from general population cohorts were reclassified to a higher and lower estimated GFR category, respectively, by the CKD-EPI equation, and the prevalence of CKD stages 3 to 5 (estimated GFR <60 mL/min/1.73 m(2)) was reduced from 8.7% to 6.3%. In estimated GFR of 45 to 59 mL/min/1.73 m(2) by the MDRD Study equation, 34.7% of participants were reclassified to estimated GFR of 60 to 89 mL/min/1.73 m(2) by the CKD-EPI equation and had lower incidence rates (per 1000 person-years) for the outcomes of interest (9.9 vs 34.5 for all-cause mortality, 2.7 vs 13.0 for cardiovascular mortality, and 0.5 vs 0.8 for ESRD) compared with those not reclassified. The corresponding adjusted hazard ratios were 0.80 (95% CI, 0.74-0.86) for all-cause mortality, 0.73 (95% CI, 0.65-0.82) for cardiovascular mortality, and 0.49 (95% CI, 0.27-0.88) for ESRD. Similar findings were observed in other estimated GFR categories by the MDRD Study equation. Net reclassification improvement based on estimated GFR categories was significantly positive for all outcomes (range, 0.06-0.13; all P < .001). Net reclassification improvement was similarly positive in most subgroups defined by age (<65 years and ≥65 years), sex, race/ethnicity (white, Asian, and black), and presence or absence of diabetes and hypertension. The results in the high-risk and CKD cohorts were largely consistent with the general population cohorts. CONCLUSION: The CKD-EPI equation classified fewer individuals as having CKD and more accurately categorized the risk for mortality and ESRD than did the MDRD Study equation across a broad range of populations.
Keywords: African Continental Ancestry Group; Aged; Algorithms; Asian Continental Ancestry Group; Cardiovascular Diseases; Cohort Studies; Decision Support Techniques; European Continental Ancestry Group; Female; Glomerular Filtration Rate; Humans; Kidney Failure, Chronic; Male; Middle Aged; Models, Theoretical; Risk Assessment; Sex Factors

Consistent directions of effect for established type 2 diabetes risk variants across populations: the population architecture using Genomics and Epidemiology (PAGE) Consortium. - Haiman, Christopher A; Fesinmeyer, Megan D; Spencer, Kylee L; Bůzková, Petra; Voruganti, V Saroja; Wan, Peggy; Haessler, Jeff; Franceschini, Nora; Monroe, Kristine R; Howard, Barbara V; Jackson, Rebecca D; Florez, Jose C; et al. (Diabetes, 2012)
Common genetic risk variants for type 2 diabetes (T2D) have primarily been identified in populations of European and Asian ancestry. We tested whether the direction of association with 20 T2D risk variants generalizes across six major racial/ethnic groups in the U.S. as part of the Population Architecture using Genomics and Epidemiology Consortium (16,235 diabetes case and 46,122 control subjects of European American, African American, Hispanic, East Asian, American Indian, and Native Hawaiian ancestry). The percentage of positive (odds ratio [OR] >1 for putative risk allele) associations ranged from 69% in American Indians to 100% in European Americans. Of the nine variants where we observed significant heterogeneity of effect by racial/ethnic group (P(heterogeneity) < 0.05), eight were positively associated with risk (OR >1) in at least five groups. The marked directional consistency of association observed for most genetic variants across populations implies a shared functional common variant in each region. Fine-mapping of all loci will be required to reveal markers of risk that are important within and across populations.
Keywords: Adult; Aged; Aged, 80 and over; Alleles; Diabetes Mellitus, Type 2; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Genotype; Humans; Male; Metagenomics; Middle Aged; Population Groups; Risk; Risk Factors

Development and validation of a coronary risk prediction model for older U.S. and European persons in the Cardiovascular Health Study and the Rotterdam Study. - Koller, Michael T; Leening, Maarten J G; Wolbers, Marcel; Steyerberg, Ewout W; Hunink, M G Myriam; Schoop, Rotraut; Hofman, Albert; Bucher, Heiner C; Psaty, Bruce M; Lloyd-Jones, Donald M; Witteman, Jacqueline C M (Ann Intern Med, 2012)
BACKGROUND: Risk scores for prediction of coronary heart disease (CHD) in older adults are needed. OBJECTIVE: To develop a sex-specific CHD risk prediction model for older adults that accounts for competing risks for death. DESIGN: 2 observational cohort studies, using data from 4946 participants in the Cardiovascular Health Study (CHS) and 4303 participants in the Rotterdam Study (RS). SETTING: Community settings in the United States (CHS) and Rotterdam, the Netherlands (RS). PARTICIPANTS: Persons aged 65 years or older who were free of cardiovascular disease. MEASUREMENTS: A composite of nonfatal myocardial infarction and coronary death. RESULTS: During a median follow-up of 16.5 and 14.9 years, 1166 CHS and 698 RS participants had CHD events, respectively. Deaths from noncoronary causes largely exceeded the number of CHD events, complicating accurate CHD risk predictions. The prediction model had moderate ability to discriminate between events and nonevents (c-statistic, 0.63 in both U.S. and European men and 0.67 and 0.68 in U.S. and European women). The model was well-calibrated; predicted risks were in good agreement with observed risks. Compared with the Framingham point scores, the prediction model classified elderly U.S. persons into higher risk categories but elderly European persons into lower risk categories. Differences in classification accuracy were not consistent and depended on cohort and sex. Adding newer cardiovascular risk markers to the model did not substantially improve performance. LIMITATION: The model may be less applicable in nonwhite populations, and the comparison Framingham model was not designed for adults older than 79 years. CONCLUSION: A CHD risk prediction model that accounts for deaths from noncoronary causes among older adults provided well-calibrated risk estimates but was not substantially more accurate than Framingham point scores. Moreover, adding newer risk markers did not improve accuracy. These findings emphasize the difficulties of predicting CHD risk in elderly persons and the need to improve these predictions. PRIMARY FUNDING SOURCE: National Heart, Lung, and Blood Institute; National Institute of Neurological Disorders and Stroke; The Netherlands Organisation for Scientific Research; and the Netherlands Organisation for Health Research and Development.
Keywords: Aged; Aged, 80 and over; Algorithms; Cause of Death; Coronary Disease; European Continental Ancestry Group; Female; Humans; Incidence; Male; Models, Statistical; Multivariate Analysis; Netherlands; Prospective Studies; Risk Assessment; Risk Factors; United States

Effect of Alzheimer's disease risk genes on trajectories of cognitive function in the Cardiovascular Health Study. - Sweet, Robert A; Seltman, Howard; Emanuel, James E; Lopez, Oscar L; Becker, James T; Bis, Joshua C; Weamer, Elise A; Demichele-Sweet, Mary Ann A; Kuller, Lewis H (Am J Psychiatry, 2012)
OBJECTIVE: The trajectory of cognitive decline in patients with late-onset Alzheimer's disease varies widely. Genetic variations in CLU, PICALM, and CR1 are associated with Alzheimer's disease, but it is unknown whether they exert their effects by altering cognitive trajectory in elderly individuals at risk for the disease. METHOD: The authors developed a Bayesian model to fit cognitive trajectories in a cohort of elderly subjects and test for genetic effects. They first validated the model's ability to detect the previously established effects of APOE ε4 alleles on age at cognitive decline and of psychosis on the rate of cognitive decline in 802 subjects from the Cardiovascular Health Cognition Study who did not have dementia at study entry and developed incident dementia during follow-up. The authors then evaluated the effects of CLU, PICALM, and CR1 on age and rate of decline in 1,831 subjects who did not have dementia at study entry and then did or did not develop incident dementia by study's end. RESULTS: The model generated robust fits to the observed cognitive trajectory data, and validation analysis supported the model's utility. CLU and CR1 were associated with more rapid cognitive decline. PICALM was associated with an earlier age at midpoint of cognitive decline. Associations remained after accounting for the effects of APOE and demographic factors. CONCLUSIONS: Evaluation of cognitive trajectories provides a powerful approach to dissecting genetic effects on the processes leading to cognitive deterioration and Alzheimer's disease.
Keywords: Age of Onset; Aged; Alleles; Alzheimer Disease; Apolipoprotein E4; Bayes Theorem; Clusterin; Cohort Studies; Dementia; Disease Progression; Female; Genetic Predisposition to Disease; Humans; Male; Models, Psychological; Monomeric Clathrin Assembly Proteins; Polymorphism, Single Nucleotide; Receptors, Complement 3b; Risk Factors

Eight genetic loci associated with variation in lipoprotein-associated phospholipase A2 mass and activity and coronary heart disease: meta-analysis of genome-wide association studies from five community-based studies. - Grallert, Harald; Dupuis, Josée; Bis, Joshua C; Dehghan, Abbas; Barbalic, Maja; Baumert, Jens; Lu, Chen; Smith, Nicholas L; Uitterlinden, André G; Roberts, Robert; Khuseyinova, Natalie; Schnabel, Renate B; et al. (Eur Heart J, 2012)
AIMS: Lipoprotein-associated phospholipase A2 (Lp-PLA2) generates proinflammatory and proatherogenic compounds in the arterial vascular wall and is a potential therapeutic target in coronary heart disease (CHD). We searched for genetic loci related to Lp-PLA2 mass or activity by a genome-wide association study as part of the Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) Consortium. METHODS AND RESULTS: In meta-analyses of findings from five population-based studies, comprising 13 664 subjects, variants at two loci (PLA2G7, CETP) were associated with Lp-PLA2 mass. The strongest signal was at rs1805017 in PLA2G7 [P = 2.4 × 10(-23), log Lp-PLA2 difference per allele (beta): 0.043]. Variants at six loci were associated with Lp-PLA2 activity (PLA2G7, APOC1, CELSR2, LDL, ZNF259, SCARB1), among which the strongest signals were at rs4420638, near the APOE-APOC1-APOC4-APOC2 cluster [P = 4.9 × 10(-30); log Lp-PLA2 difference per allele (beta): -0.054]. There were no significant gene-environment interactions between these eight polymorphisms associated with Lp-PLA2 mass or activity and age, sex, body mass index, or smoking status. Four of the polymorphisms (in APOC1, CELSR2, SCARB1, ZNF259), but not PLA2G7, were significantly associated with CHD in a second study. CONCLUSION: Levels of Lp-PLA2 mass and activity were associated with PLA2G7, the gene coding for this protein. Lipoprotein-associated phospholipase A2 activity was also strongly associated with genetic variants related to low-density lipoprotein cholesterol levels.
Keywords: 1-Alkyl-2-acetylglycerophosphocholine Esterase; Aged; Coronary Artery Disease; Coronary Disease; Female; Genetic Loci; Genome-Wide Association Study; Humans; Male; Middle Aged; Phospholipases A2; Polymorphism, Single Nucleotide

Evaluation of the metabochip genotyping array in African Americans and implications for fine mapping of GWAS-identified loci: the PAGE study. - Buyske, Steven; Wu, Ying; Carty, Cara L; Cheng, Iona; Assimes, Themistocles L; Dumitrescu, Logan; Hindorff, Lucia A; Mitchell, Sabrina; Ambite, Jose Luis; Boerwinkle, Eric; Bůzková, Petra; Carlson, Chris S; et al. (PLoS One, 2012)
The Metabochip is a custom genotyping array designed for replication and fine mapping of metabolic, cardiovascular, and anthropometric trait loci and includes low frequency variation content identified from the 1000 Genomes Project. It has 196,725 SNPs concentrated in 257 genomic regions. We evaluated the Metabochip in 5,863 African Americans; 89% of all SNPs passed rigorous quality control with a call rate of 99.9%. Two examples illustrate the value of fine mapping with the Metabochip in African-ancestry populations. At CELSR2/PSRC1/SORT1, we found the strongest associated SNP for LDL-C to be rs12740374 (p = 3.5 × 10(-11)), a SNP indistinguishable from multiple SNPs in European ancestry samples due to high correlation. Its distinct signal supports functional studies elsewhere suggesting a causal role in LDL-C. At CETP we found rs17231520, with risk allele frequency 0.07 in African Americans, to be associated with HDL-C (p = 7.2 × 10(-36)). This variant is very rare in Europeans and not tagged in common GWAS arrays, but was identified as associated with HDL-C in African Americans in a single-gene study. Our results, one narrowing the risk interval and the other revealing an associated variant not found in Europeans, demonstrate the advantages of high-density genotyping of common and rare variation for fine mapping of trait loci in African American samples.
Keywords: African Americans; Cardiovascular Diseases; Cholesterol Ester Transfer Proteins; Cholesterol, HDL; Cholesterol, LDL; Chromosomes, Human; Cohort Studies; Gene Frequency; Genome-Wide Association Study; Genotype; Humans; Metabolic Diseases; Polymorphism, Single Nucleotide; Quantitative Trait Loci

Fine-mapping and initial characterization of QT interval loci in African Americans. - Avery, Christy L; Sethupathy, Praveen; Buyske, Steven; He, Qianchuan; Lin, Dan-Yu; Arking, Dan E; Carty, Cara L; Duggan, David; Fesinmeyer, Megan D; Hindorff, Lucia A; Jeff, Janina M; Klein, Liviu; et al. (PLoS Genet, 2012)
The QT interval (QT) is heritable and its prolongation is a risk factor for ventricular tachyarrhythmias and sudden death. Most genetic studies of QT have examined European ancestral populations; however, the increased genetic diversity in African Americans provides opportunities to narrow association signals and identify population-specific variants. We therefore evaluated 6,670 SNPs spanning eleven previously identified QT loci in 8,644 African American participants from two Population Architecture using Genomics and Epidemiology (PAGE) studies: the Atherosclerosis Risk in Communities study and Women's Health Initiative Clinical Trial. Of the fifteen known independent QT variants at the eleven previously identified loci, six were significantly associated with QT in African American populations (P≤1.20×10(-4)): ATP1B1, PLN1, KCNQ1, NDRG4, and two NOS1AP independent signals. We also identified three population-specific signals significantly associated with QT in African Americans (P≤1.37×10(-5)): one at NOS1AP and two at ATP1B1. Linkage disequilibrium (LD) patterns in African Americans assisted in narrowing the region likely to contain the functional variants for several loci. For example, African American LD patterns showed that 0 SNPs were in LD with NOS1AP signal rs12143842, compared with European LD patterns that indicated 87 SNPs, which spanned 114.2 Kb, were in LD with rs12143842. Finally, bioinformatic-based characterization of the nine African American signals pointed to functional candidates located exclusively within non-coding regions, including predicted binding sites for transcription factors such as TBX5, which has been implicated in cardiac structure and conductance. In this detailed evaluation of QT loci, we identified several African Americans SNPs that better define the association with QT and successfully narrowed intervals surrounding established loci. These results demonstrate that the same loci influence variation in QT across multiple populations, that novel signals exist in African Americans, and that the SNPs identified as strong candidates for functional evaluation implicate gene regulatory dysfunction in QT prolongation.
Keywords: African Americans; Aged; Computational Biology; Electrocardiography; European Continental Ancestry Group; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Linkage Disequilibrium; Male; Metagenomics; Middle Aged; Polymorphism, Single Nucleotide; Quantitative Trait Loci; Quantitative Trait, Heritable; Risk Factors; Tachycardia; United States

FTO genotype is associated with phenotypic variability of body mass index. - Yang, Jian; Loos, Ruth J F; Powell, Joseph E; Medland, Sarah E; Speliotes, Elizabeth K; Chasman, Daniel I; Rose, Lynda M; Thorleifsson, Gudmar; Steinthorsdottir, Valgerdur; Mägi, Reedik; Waite, Lindsay; Smith, Albert Vernon; et al. (Nature, 2012)
There is evidence across several species for genetic control of phenotypic variation of complex traits, such that the variance among phenotypes is genotype dependent. Understanding genetic control of variability is important in evolutionary biology, agricultural selection programmes and human medicine, yet for complex traits, no individual genetic variants associated with variance, as opposed to the mean, have been identified. Here we perform a meta-analysis of genome-wide association studies of phenotypic variation using ∼170,000 samples on height and body mass index (BMI) in human populations. We report evidence that the single nucleotide polymorphism (SNP) rs7202116 at the FTO gene locus, which is known to be associated with obesity (as measured by mean BMI for each rs7202116 genotype), is also associated with phenotypic variability. We show that the results are not due to scale effects or other artefacts, and find no other experiment-wise significant evidence for effects on variability, either at loci other than FTO for BMI or at any locus for height. The difference in variance for BMI among individuals with opposite homozygous genotypes at the FTO locus is approximately 7%, corresponding to a difference of ∼0.5 kilograms in the standard deviation of weight. Our results indicate that genetic variants can be discovered that are associated with variability, and that between-person variability in obesity can partly be explained by the genotype at the FTO locus. The results are consistent with reported FTO by environment interactions for BMI, possibly mediated by DNA methylation. Our BMI results for other SNPs and our height results for all SNPs suggest that most genetic variants, including those that influence mean height or mean BMI, are not associated with phenotypic variance, or that their effects on variability are too small to detect even with samples sizes greater than 100,000.
Keywords: Alpha-Ketoglutarate-Dependent Dioxygenase FTO; Body Height; Body Mass Index; Co-Repressor Proteins; Female; Genetic Variation; Genome-Wide Association Study; Humans; Male; Nerve Tissue Proteins; Phenotype; Polymorphism, Single Nucleotide; Proteins; Repressor Proteins

Genetic determinants of the ankle-brachial index: a meta-analysis of a cardiovascular candidate gene 50K SNP panel in the candidate gene association resource (CARe) consortium. - Wassel, Christina L; Lamina, Claudia; Nambi, Vijay; Coassin, Stefan; Mukamal, Kenneth J; Ganesh, Santhi K; Jacobs, David R; Franceschini, Nora; Papanicolaou, George J; Gibson, Quince; Yanek, Lisa R; van der Harst, Pim; et al. (Atherosclerosis, 2012)
BACKGROUND: Candidate gene association studies for peripheral artery disease (PAD), including subclinical disease assessed with the ankle-brachial index (ABI), have been limited by the modest number of genes examined. We conducted a two stage meta-analysis of ∼50,000 SNPs across ∼2100 candidate genes to identify genetic variants for ABI. METHODS AND RESULTS: We studied subjects of European ancestry from 8 studies (n=21,547, 55% women, mean age 44-73 years) and African American ancestry from 5 studies (n=7267, 60% women, mean age 41-73 years) involved in the candidate gene association resource (CARe) consortium. In each ethnic group, additive genetic models were used (with each additional copy of the minor allele corresponding to the given beta) to test each SNP for association with continuous ABI (excluding ABI>1.40) and PAD (defined as ABI<0.90) using linear or logistic regression with adjustment for known PAD risk factors and population stratification. We then conducted a fixed-effects inverse-variance weighted meta-analyses considering a p<2×10(-6) to denote statistical significance. RESULTS: In the European ancestry discovery meta-analyses, rs2171209 in SYTL3 (β=-0.007, p=6.02×10(-7)) and rs290481 in TCF7L2 (β=-0.008, p=7.01×10(-7)) were significantly associated with ABI. None of the SNP associations for PAD were significant, though a SNP in CYP2B6 (p=4.99×10(-5)) was among the strongest associations. These 3 genes are linked to key PAD risk factors (lipoprotein(a), type 2 diabetes, and smoking behavior, respectively). We sought replication in 6 population-based and 3 clinical samples (n=15,440) for rs290481 and rs2171209. However, in the replication stage (rs2171209, p=0.75; rs290481, p=0.19) and in the combined discovery and replication analysis the SNP-ABI associations were no longer significant (rs2171209, p=1.14×10(-3); rs290481, p=8.88×10(-5)). In African Americans, none of the SNP associations for ABI or PAD achieved an experiment-wide level of significance. CONCLUSIONS: Genetic determinants of ABI and PAD remain elusive. Follow-up of these preliminary findings may uncover important biology given the known gene-risk factor associations. New and more powerful approaches to PAD gene discovery are warranted.
Keywords: Adult; African Americans; Aged; Ankle Brachial Index; Aryl Hydrocarbon Hydroxylases; Cytochrome P-450 CYP2B6; European Continental Ancestry Group; Female; Humans; Male; Middle Aged; Oxidoreductases, N-Demethylating; Peripheral Arterial Disease; Polymorphism, Single Nucleotide; Risk Factors; Transcription Factor 7-Like 2 Protein

Genetic risk factors for ischaemic stroke and its subtypes (the METASTROKE collaboration): a meta-analysis of genome-wide association studies. - Traylor, Matthew; Farrall, Martin; Holliday, Elizabeth G; Sudlow, Cathie; Hopewell, Jemma C; Cheng, Yu-Ching; Fornage, Myriam; Ikram, M Arfan; Malik, Rainer; Bevan, Steve; Thorsteinsdottir, Unnur; Nalls, Mike A; et al. (Lancet Neurol, 2012)
BACKGROUND: Various genome-wide association studies (GWAS) have been done in ischaemic stroke, identifying a few loci associated with the disease, but sample sizes have been 3500 cases or less. We established the METASTROKE collaboration with the aim of validating associations from previous GWAS and identifying novel genetic associations through meta-analysis of GWAS datasets for ischaemic stroke and its subtypes. METHODS: We meta-analysed data from 15 ischaemic stroke cohorts with a total of 12 389 individuals with ischaemic stroke and 62 004 controls, all of European ancestry. For the associations reaching genome-wide significance in METASTROKE, we did a further analysis, conditioning on the lead single nucleotide polymorphism in every associated region. Replication of novel suggestive signals was done in 13 347 cases and 29 083 controls. FINDINGS: We verified previous associations for cardioembolic stroke near PITX2 (p=2·8×10(-16)) and ZFHX3 (p=2·28×10(-8)), and for large-vessel stroke at a 9p21 locus (p=3·32×10(-5)) and HDAC9 (p=2·03×10(-12)). Additionally, we verified that all associations were subtype specific. Conditional analysis in the three regions for which the associations reached genome-wide significance (PITX2, ZFHX3, and HDAC9) indicated that all the signal in each region could be attributed to one risk haplotype. We also identified 12 potentially novel loci at p<5×10(-6). However, we were unable to replicate any of these novel associations in the replication cohort. INTERPRETATION: Our results show that, although genetic variants can be detected in patients with ischaemic stroke when compared with controls, all associations we were able to confirm are specific to a stroke subtype. This finding has two implications. First, to maximise success of genetic studies in ischaemic stroke, detailed stroke subtyping is required. Second, different genetic pathophysiological mechanisms seem to be associated with different stroke subtypes. FUNDING: Wellcome Trust, UK Medical Research Council (MRC), Australian National and Medical Health Research Council, National Institutes of Health (NIH) including National Heart, Lung and Blood Institute (NHLBI), the National Institute on Aging (NIA), the National Human Genome Research Institute (NHGRI), and the National Institute of Neurological Disorders and Stroke (NINDS).
Keywords: Brain Ischemia; Databases, Genetic; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Risk Factors; Stroke

Genetic variants and associations of 25-hydroxyvitamin D concentrations with major clinical outcomes. - Levin, Gregory P; Robinson-Cohen, Cassianne; de Boer, Ian H; Houston, Denise K; Lohman, Kurt; Liu, Yongmei; Kritchevsky, Stephen B; Cauley, Jane A; Tanaka, Toshiko; Ferrucci, Luigi; Bandinelli, Stefania; Patel, Kushang V; et al. (JAMA, 2012)
CONTEXT: Lower serum 25-hydroxyvitamin D concentrations are associated with greater risks of many chronic diseases across large, prospective community-based studies. Substrate 25-hydroxyvitamin D must be converted to 1,25-dihydroxyvitamin D for full biological activity, and complex metabolic pathways suggest that interindividual variability in vitamin D metabolism may alter the clinical consequences of measured serum 25-hydroxyvitamin D. OBJECTIVE: To investigate whether common variation within genes encoding the vitamin D-binding protein, megalin, cubilin, CYP27B1, CYP24A1, and the vitamin D receptor (VDR) modify associations of low 25-hydroxyvitamin D with major clinical outcomes. DESIGN, SETTING, AND PARTICIPANTS: Examination of 141 single-nucleotide polymorphisms in a discovery cohort of 1514 white participants (who were recruited from 4 US regions) from the community-based Cardiovascular Health Study. Participants had serum 25-hydroxyvitamin D measurements in 1992-1993 and were followed up for a median of 11 years (through 2006). Replication meta-analyses were conducted across the independent, community-based US Health, Aging, and Body Composition (n = 922; follow-up: 1998-1999 through 2005), Italian Invecchiare in Chianti (n = 835; follow-up: 1998-2000 through 2006), and Swedish Uppsala Longitudinal Study of Adult Men (n = 970; follow-up: 1991-1995 through 2008) cohort studies. MAIN OUTCOME MEASURE: Composite outcome of incident hip facture, myocardial infarction, cancer, and mortality over long-term follow-up. RESULTS: Interactions between 5 single-nucleotide polymorphisms and low 25-hydroxyvitamin D concentration were identified in the discovery phase and 1 involving a variant in the VDR gene replicated in independent meta-analysis. Among Cardiovascular Health Study participants, low 25-hydroxyvitamin D concentration was associated with hazard ratios for risk of the composite outcome of 1.40 (95% CI, 1.12-1.74) for those who had 1 minor allele at rs7968585 and 1.82 (95% CI, 1.31-2.54) for those with 2 minor alleles at rs7968585. In contrast, there was no evidence of an association (estimated hazard ratio, 0.93 [95% CI, 0.70-1.24]) among participants who had 0 minor alleles at this single-nucleotide polymorphism. CONCLUSION: Known associations of low 25-hydroxyvitamin D with major health outcomes may vary according to common genetic differences in the vitamin D receptor.
Keywords: 25-Hydroxyvitamin D3 1-alpha-Hydroxylase; Aged; Chronic Disease; Cohort Studies; Female; Genetic Variation; Genotype; Hip Fractures; Humans; Low Density Lipoprotein Receptor-Related Protein-2; Male; Meta-Analysis as Topic; Myocardial Infarction; Neoplasms; Polymorphism, Single Nucleotide; Receptors, Calcitriol; Receptors, Cell Surface; Risk; Steroid Hydroxylases; Vitamin D; Vitamin D3 24-Hydroxylase

Genetic variants in Arhgef11 are associated with kidney injury in the Dahl salt-sensitive rat. - Williams, Jan M; Johnson, Ashley C; Stelloh, Cary; Dreisbach, Albert W; Franceschini, Nora; Regner, Kevin R; Townsend, Raymond R; Roman, Richard J; Garrett, Michael R (Hypertension, 2012)
A previous genetic analysis comparing the Dahl salt-sensitive (S) rat with the spontaneously hypertensive rat identified a major locus on chromosome 2 that influences proteinuria in the S rat. In the present study, blood pressure, proteinuria, and renal hemodynamics were evaluated in congenic strains with small segments of the protective spontaneously hypertensive rat genome on the S background. Proteinuria and renal function were significantly improved in the congenic strains compared with the S. The causative locus interval was narrowed to <375 kb on the basis of congenic strains, haplotype data, comparative mapping, and concordance with human genetic studies. Sequencing of the coding region of genes in this region identified 36 single nucleotide polymorphisms (13 nonsynonymous and 23 synonymous). Gene expression profiling indicated that only a few genes exhibited differential expression. Arhgef11, Pear1, and Sh2d2 were identified as important candidate genes that may be linked to kidney injury in the S rat. In particular, Arhgef11 plays an important role in the activation of the Rho-ROCK signaling pathway. Inhibition of this pathway using fasudil resulted in a significant reduction of proteinuria in treated S rats (compared with untreated S). However, no difference was observed between treated or untreated spontaneously hypertensive rat or congenic strains. The homologous region in humans was found to be associated with estimated glomerular filtration rate in the Candidate Gene Association Resource population. In summary, these findings demonstrate that allelic variants in Arhgef11, acting through the Rho-ROCK pathway, could influence kidney injury in the S as well as provide insight into human kidney disease.
Keywords: 1-(5-Isoquinolinesulfonyl)-2-Methylpiperazine; Animals; Animals, Congenic; Blood Pressure; Blotting, Western; Chromosome Mapping; Gene Expression Profiling; Genetic Predisposition to Disease; Guanine Nucleotide Exchange Factors; Humans; Kidney; Kidney Diseases; Male; Polymorphism, Single Nucleotide; Protein Kinase Inhibitors; Proteinuria; Quantitative Trait Loci; Rats; Rats, Inbred Dahl; Rats, Inbred SHR; Renal Circulation; Reverse Transcriptase Polymerase Chain Reaction; rho-Associated Kinases; rhoA GTP-Binding Protein; Signal Transduction

Genome-wide association and functional follow-up reveals new loci for kidney function. - Pattaro, Cristian; Köttgen, Anna; Teumer, Alexander; Garnaas, Maija; Böger, Carsten A; Fuchsberger, Christian; Olden, Matthias; Chen, Ming-Huei; Tin, Adrienne; Taliun, Daniel; Li, Man; Gao, Xiaoyi; et al. (PLoS Genet, 2012)
Chronic kidney disease (CKD) is an important public health problem with a genetic component. We performed genome-wide association studies in up to 130,600 European ancestry participants overall, and stratified for key CKD risk factors. We uncovered 6 new loci in association with estimated glomerular filtration rate (eGFR), the primary clinical measure of CKD, in or near MPPED2, DDX1, SLC47A1, CDK12, CASP9, and INO80. Morpholino knockdown of mpped2 and casp9 in zebrafish embryos revealed podocyte and tubular abnormalities with altered dextran clearance, suggesting a role for these genes in renal function. By providing new insights into genes that regulate renal function, these results could further our understanding of the pathogenesis of CKD.
Keywords: African Americans; Aged; Animals; Caspase 9; Cyclin-Dependent Kinases; DEAD-box RNA Helicases; DNA Helicases; European Continental Ancestry Group; Female; Follow-Up Studies; Gene Knockdown Techniques; Genome-Wide Association Study; Glomerular Filtration Rate; Humans; Kidney; Kidney Failure, Chronic; Male; Middle Aged; Phosphoric Diester Hydrolases; Zebrafish

Genome-wide association studies identify CHRNA5/3 and HTR4 in the development of airflow obstruction. - Wilk, Jemma B; Shrine, Nick R G; Loehr, Laura R; Zhao, Jing Hua; Manichaikul, Ani; Lopez, Lorna M; Smith, Albert Vernon; Heckbert, Susan R; Smolonska, Joanna; Tang, Wenbo; Loth, Daan W; Curjuric, Ivan; et al. (Am J Respir Crit Care Med, 2012)
RATIONALE: Genome-wide association studies (GWAS) have identified loci influencing lung function, but fewer genes influencing chronic obstructive pulmonary disease (COPD) are known. OBJECTIVES: Perform meta-analyses of GWAS for airflow obstruction, a key pathophysiologic characteristic of COPD assessed by spirometry, in population-based cohorts examining all participants, ever smokers, never smokers, asthma-free participants, and more severe cases. METHODS: Fifteen cohorts were studied for discovery (3,368 affected; 29,507 unaffected), and a population-based family study and a meta-analysis of case-control studies were used for replication and regional follow-up (3,837 cases; 4,479 control subjects). Airflow obstruction was defined as FEV(1) and its ratio to FVC (FEV(1)/FVC) both less than their respective lower limits of normal as determined by published reference equations. MEASUREMENTS AND MAIN RESULTS: The discovery meta-analyses identified one region on chromosome 15q25.1 meeting genome-wide significance in ever smokers that includes AGPHD1, IREB2, and CHRNA5/CHRNA3 genes. The region was also modestly associated among never smokers. Gene expression studies confirmed the presence of CHRNA5/3 in lung, airway smooth muscle, and bronchial epithelial cells. A single-nucleotide polymorphism in HTR4, a gene previously related to FEV(1)/FVC, achieved genome-wide statistical significance in combined meta-analysis. Top single-nucleotide polymorphisms in ADAM19, RARB, PPAP2B, and ADAMTS19 were nominally replicated in the COPD meta-analysis. CONCLUSIONS: These results suggest an important role for the CHRNA5/3 region as a genetic risk factor for airflow obstruction that may be independent of smoking and implicate the HTR4 gene in the etiology of airflow obstruction.
Keywords: Aged; Female; Forced Expiratory Volume; Genome-Wide Association Study; Humans; Male; Middle Aged; Nerve Tissue Proteins; Polymorphism, Single Nucleotide; Pulmonary Disease, Chronic Obstructive; Receptors, Nicotinic; Receptors, Serotonin, 5-HT4; Smoking; Vital Capacity

Genome-wide association study for circulating levels of PAI-1 provides novel insights into its regulation. - Huang, Jie; Sabater-Lleal, Maria; Asselbergs, Folkert W; Tregouet, David; Shin, So-Youn; Ding, Jingzhong; Baumert, Jens; Oudot-Mellakh, Tiphaine; Folkersen, Lasse; Johnson, Andrew D; Smith, Nicholas L; Williams, Scott M; et al. (Blood, 2012)
We conducted a genome-wide association study to identify novel associations between genetic variants and circulating plasminogen activator inhibitor-1 (PAI-1) concentration, and examined functional implications of variants and genes that were discovered. A discovery meta-analysis was performed in 19 599 subjects, followed by replication analysis of genome-wide significant (P < 5 × 10(-8)) single nucleotide polymorphisms (SNPs) in 10 796 independent samples. We further examined associations with type 2 diabetes and coronary artery disease, assessed the functional significance of the SNPs for gene expression in human tissues, and conducted RNA-silencing experiments for one novel association. We confirmed the association of the 4G/5G proxy SNP rs2227631 in the promoter region of SERPINE1 (7q22.1) and discovered genome-wide significant associations at 3 additional loci: chromosome 7q22.1 close to SERPINE1 (rs6976053, discovery P = 3.4 × 10(-10)); chromosome 11p15.2 within ARNTL (rs6486122, discovery P = 3.0 × 10(-8)); and chromosome 3p25.2 within PPARG (rs11128603, discovery P = 2.9 × 10(-8)). Replication was achieved for the 7q22.1 and 11p15.2 loci. There was nominal association with type 2 diabetes and coronary artery disease at ARNTL (P < .05). Functional studies identified MUC3 as a candidate gene for the second association signal on 7q22.1. In summary, SNPs in SERPINE1 and ARNTL and an SNP associated with the expression of MUC3 were robustly associated with circulating levels of PAI-1.
Keywords: Adaptor Proteins, Signal Transducing; ARNTL Transcription Factors; ATPases Associated with Diverse Cellular Activities; Cell Line; Cell Line, Tumor; Cohort Studies; Coronary Artery Disease; Diabetes Mellitus, Type 2; Gene Expression Profiling; Gene Expression Regulation; Gene Frequency; Genome-Wide Association Study; Genotype; Humans; LIM Domain Proteins; Meta-Analysis as Topic; Monocytes; Mucin-3; Plasminogen Activator Inhibitor 1; Polymorphism, Single Nucleotide; PPAR gamma; Proteasome Endopeptidase Complex; RNA Interference; Transcription Factors

Genome-wide joint meta-analysis of SNP and SNP-by-smoking interaction identifies novel loci for pulmonary function. - Hancock, Dana B; Soler Artigas, Maria; Gharib, Sina A; Henry, Amanda; Manichaikul, Ani; Ramasamy, Adaikalavan; Loth, Daan W; Imboden, Medea; Koch, Beate; McArdle, Wendy L; Smith, Albert V; Smolonska, Joanna; et al. (PLoS Genet, 2012)
Genome-wide association studies have identified numerous genetic loci for spirometic measures of pulmonary function, forced expiratory volume in one second (FEV(1)), and its ratio to forced vital capacity (FEV(1)/FVC). Given that cigarette smoking adversely affects pulmonary function, we conducted genome-wide joint meta-analyses (JMA) of single nucleotide polymorphism (SNP) and SNP-by-smoking (ever-smoking or pack-years) associations on FEV(1) and FEV(1)/FVC across 19 studies (total N = 50,047). We identified three novel loci not previously associated with pulmonary function. SNPs in or near DNER (smallest P(JMA = )5.00×10(-11)), HLA-DQB1 and HLA-DQA2 (smallest P(JMA = )4.35×10(-9)), and KCNJ2 and SOX9 (smallest P(JMA = )1.28×10(-8)) were associated with FEV(1)/FVC or FEV(1) in meta-analysis models including SNP main effects, smoking main effects, and SNP-by-smoking (ever-smoking or pack-years) interaction. The HLA region has been widely implicated for autoimmune and lung phenotypes, unlike the other novel loci, which have not been widely implicated. We evaluated DNER, KCNJ2, and SOX9 and found them to be expressed in human lung tissue. DNER and SOX9 further showed evidence of differential expression in human airway epithelium in smokers compared to non-smokers. Our findings demonstrated that joint testing of SNP and SNP-by-environment interaction identified novel loci associated with complex traits that are missed when considering only the genetic main effects.
Keywords: Forced Expiratory Volume; Gene Expression; Genome, Human; Genome-Wide Association Study; HLA-DQ Antigens; HLA-DQ beta-Chains; Humans; Lung; Nerve Tissue Proteins; Polymorphism, Single Nucleotide; Potassium Channels, Inwardly Rectifying; Pulmonary Disease, Chronic Obstructive; Receptors, Cell Surface; Smoking; SOX9 Transcription Factor; Vital Capacity

Genome-wide meta-analyses of smoking behaviors in African Americans. - David, S P; Hamidovic, A; Chen, G K; Bergen, A W; Wessel, J; Kasberger, J L; Brown, W M; Petruzella, S; Thacker, E L; Kim, Y; Nalls, M A; Tranah, G J; et al. (Transl Psychiatry, 2012)
The identification and exploration of genetic loci that influence smoking behaviors have been conducted primarily in populations of the European ancestry. Here we report results of the first genome-wide association study meta-analysis of smoking behavior in African Americans in the Study of Tobacco in Minority Populations Genetics Consortium (n = 32,389). We identified one non-coding single-nucleotide polymorphism (SNP; rs2036527[A]) on chromosome 15q25.1 associated with smoking quantity (cigarettes per day), which exceeded genome-wide significance (β = 0.040, s.e. = 0.007, P = 1.84 × 10(-8)). This variant is present in the 5'-distal enhancer region of the CHRNA5 gene and defines the primary index signal reported in studies of the European ancestry. No other SNP reached genome-wide significance for smoking initiation (SI, ever vs never smoking), age of SI, or smoking cessation (SC, former vs current smoking). Informative associations that approached genome-wide significance included three modestly correlated variants, at 15q25.1 within PSMA4, CHRNA5 and CHRNA3 for smoking quantity, which are associated with a second signal previously reported in studies in European ancestry populations, and a signal represented by three SNPs in the SPOCK2 gene on chr10q22.1. The association at 15q25.1 confirms this region as an important susceptibility locus for smoking quantity in men and women of African ancestry. Larger studies will be needed to validate the suggestive loci that did not reach genome-wide significance and further elucidate the contribution of genetic variation to disparities in cigarette consumption, SC and smoking-attributable disease between African Americans and European Americans.
Keywords: Adult; African Americans; Aged; Chromosomes, Human, Pair 10; Chromosomes, Human, Pair 15; Female; Genetic Loci; Genetic Predisposition to Disease; Genetic Variation; Genome-Wide Association Study; Genotype; Humans; Male; Middle Aged; Nerve Tissue Proteins; Phenotype; Polymorphism, Single Nucleotide; Proteoglycans; Receptors, Nicotinic; Smoking; Statistics as Topic

Genome-wide meta-analysis identifies 56 bone mineral density loci and reveals 14 loci associated with risk of fracture. - Estrada, Karol; Styrkarsdottir, Unnur; Evangelou, Evangelos; Hsu, Yi-Hsiang; Duncan, Emma L; Ntzani, Evangelia E; Oei, Ling; Albagha, Omar M E; Amin, Najaf; Kemp, John P; Koller, Daniel L; Li, Guo; et al. (Nat Genet, 2012)
Bone mineral density (BMD) is the most widely used predictor of fracture risk. We performed the largest meta-analysis to date on lumbar spine and femoral neck BMD, including 17 genome-wide association studies and 32,961 individuals of European and east Asian ancestry. We tested the top BMD-associated markers for replication in 50,933 independent subjects and for association with risk of low-trauma fracture in 31,016 individuals with a history of fracture (cases) and 102,444 controls. We identified 56 loci (32 new) associated with BMD at genome-wide significance (P < 5 × 10(-8)). Several of these factors cluster within the RANK-RANKL-OPG, mesenchymal stem cell differentiation, endochondral ossification and Wnt signaling pathways. However, we also discovered loci that were localized to genes not known to have a role in bone biology. Fourteen BMD-associated loci were also associated with fracture risk (P < 5 × 10(-4), Bonferroni corrected), of which six reached P < 5 × 10(-8), including at 18p11.21 (FAM210A), 7q21.3 (SLC25A13), 11q13.2 (LRP5), 4q22.1 (MEPE), 2p16.2 (SPTBN1) and 10q21.1 (DKK1). These findings shed light on the genetic architecture and pathophysiological mechanisms underlying BMD variation and fracture susceptibility.
Keywords: Bone Density; Computational Biology; European Continental Ancestry Group; Extracellular Matrix Proteins; Female; Femur Neck; Fractures, Bone; Gene Expression Profiling; Genetic Predisposition to Disease; Genome-Wide Association Study; Genotype; Glycoproteins; Humans; Intercellular Signaling Peptides and Proteins; Low Density Lipoprotein Receptor-Related Protein-5; Lumbar Vertebrae; Male; Mitochondrial Membrane Transport Proteins; Osteoporosis; Phosphoproteins; Polymorphism, Single Nucleotide; Quantitative Trait Loci; Risk Factors; Spectrin

Impact of ancestry and common genetic variants on QT interval in African Americans. - Smith, J Gustav; Avery, Christy L; Evans, Daniel S; Nalls, Michael A; Meng, Yan A; Smith, Erin N; Palmer, Cameron; Tanaka, Toshiko; Mehra, Reena; Butler, Anne M; Young, Taylor; Buxbaum, Sarah G; et al. (Circ Cardiovasc Genet, 2012)
BACKGROUND: Ethnic differences in cardiac arrhythmia incidence have been reported, with a particularly high incidence of sudden cardiac death and low incidence of atrial fibrillation in individuals of African ancestry. We tested the hypotheses that African ancestry and common genetic variants are associated with prolonged duration of cardiac repolarization, a central pathophysiological determinant of arrhythmia, as measured by the electrocardiographic QT interval. METHODS AND RESULTS: First, individual estimates of African and European ancestry were inferred from genome-wide single-nucleotide polymorphism (SNP) data in 7 population-based cohorts of African Americans (n=12,097) and regressed on measured QT interval from ECGs. Second, imputation was performed for 2.8 million SNPs, and a genome-wide association study of QT interval was performed in 10 cohorts (n=13,105). There was no evidence of association between genetic ancestry and QT interval (P=0.94). Genome-wide significant associations (P<2.5 × 10(-8)) were identified with SNPs at 2 loci, upstream of the genes NOS1AP (rs12143842, P=2 × 10(-15)) and ATP1B1 (rs1320976, P=2 × 10(-10)). The most significant SNP in NOS1AP was the same as the strongest SNP previously associated with QT interval in individuals of European ancestry. Low probability values (P<10(-5)) were observed for SNPs at several other loci previously identified in genome-wide association studies in individuals of European ancestry, including KCNQ1, KCNH2, LITAF, and PLN. CONCLUSIONS: We observed no difference in duration of cardiac repolarization with global genetic indices of African American ancestry. In addition, our genome-wide association study extends the association of polymorphisms at several loci associated with repolarization in individuals of European ancestry to include individuals of African ancestry.
Keywords: Adult; African Americans; Aged; Electrocardiography; European Continental Ancestry Group; Female; Genealogy and Heraldry; Genetic Variation; Genome, Human; Genome-Wide Association Study; Humans; Male; Middle Aged; Polymorphism, Single Nucleotide

Large-scale association analyses identify new loci influencing glycemic traits and provide insight into the underlying biological pathways. - Scott, Robert A; Lagou, Vasiliki; Welch, Ryan P; Wheeler, Eleanor; Montasser, May E; Luan, Jian'an; Mägi, Reedik; Strawbridge, Rona J; Rehnberg, Emil; Gustafsson, Stefan; Kanoni, Stavroula; Rasmussen-Torvik, Laura J; et al. (Nat Genet, 2012)
Through genome-wide association meta-analyses of up to 133,010 individuals of European ancestry without diabetes, including individuals newly genotyped using the Metabochip, we have increased the number of confirmed loci influencing glycemic traits to 53, of which 33 also increase type 2 diabetes risk (q < 0.05). Loci influencing fasting insulin concentration showed association with lipid levels and fat distribution, suggesting impact on insulin resistance. Gene-based analyses identified further biologically plausible loci, suggesting that additional loci beyond those reaching genome-wide significance are likely to represent real associations. This conclusion is supported by an excess of directionally consistent and nominally significant signals between discovery and follow-up studies. Functional analysis of these newly discovered loci will further improve our understanding of glycemic control.
Keywords: Adult; Animals; Blood Glucose; Fasting; Female; Gene Frequency; Genome-Wide Association Study; Humans; Insulin; Male; Metabolic Networks and Pathways; Mice; Osmolar Concentration; Quantitative Trait Loci

Lifetime risk and years lived free of total cardiovascular disease. - Wilkins, John T; Ning, Hongyan; Berry, Jarett; Zhao, Lihui; Dyer, Alan R; Lloyd-Jones, Donald M (JAMA, 2012)
CONTEXT: Estimates of lifetime risk for total cardiovascular disease (CVD) may provide projections of the future population burden of CVD and may assist in clinician-patient risk communication. To date, no lifetime risk estimates of total CVD have been reported. OBJECTIVES: To calculate lifetime risk estimates of total CVD by index age (45, 55, 65, 75 years) and risk factor strata and to estimate years lived free of CVD across risk factor strata. DESIGN, SETTING, AND PARTICIPANTS: Pooled survival analysis of as many as 905,115 person-years of data from 1964 through 2008 from 5 National Heart, Lung, and Blood Institute-funded community-based cohorts: Framingham Heart Study, Framingham Offspring Study, Atherosclerosis Risk in Communities Study, Chicago Heart Association Detection Project in Industry Study, and Cardiovascular Health Study. All participants were free of CVD at baseline with risk factor data (blood pressure [BP], total cholesterol [TC], diabetes, and smoking status) and total CVD outcome data. MAIN OUTCOME MEASURES: Any total CVD event (including fatal and nonfatal coronary heart disease, all forms of stroke, congestive heart failure, and other CVD deaths). RESULTS: At an index age of 45 years, overall lifetime risk for total CVD was 60.3% (95% CI, 59.3%-61.2%) for men and 55.6% (95% CI, 54.5%-56.7%) for women. Men had higher lifetime risk estimates than women across all index ages. At index ages 55 and 65 years, men and women with at least 1 elevated risk factor (BP, 140-149/90-99 mm Hg; or TC, 200-239 mg/dL; but no diabetes or smoking), 1 major risk factor, or at least 2 major risk factors (BP, ≥160/100 mm Hg or receiving treatment; TC, ≥240 mg/dL or receiving treatment; diabetes mellitus; or current smoking) had lifetime risk estimates to age 95 years that exceeded 50%. Despite an optimal risk factor profile (BP, <120/80 mm Hg; TC, <180 mg/dL; and no smoking or diabetes), men and women at the index age of 55 years had lifetime risks (through 85 years of age) for total CVD of greater than 40% and 30%, respectively. Compared with participants with at least 2 major risk factors, those with an optimal risk factor profile lived up to 14 years longer free of total CVD. CONCLUSIONS: Lifetime risk estimates for total CVD were high (>30%) for all individuals, even those with optimal risk factors in middle age. However, maintenance of optimal risk factor levels in middle age was associated with substantially longer morbidity-free survival.
Keywords: Adult; Aged; Blood Pressure; Cardiovascular Diseases; Cohort Studies; Diabetes Mellitus; Female; Forecasting; Humans; Kaplan-Meier Estimate; Male; Middle Aged; Morbidity; Risk; Risk Factors; Smoking

Lipid-related markers and cardiovascular disease prediction. - Di Angelantonio, Emanuele; Gao, Pei; Pennells, Lisa; Kaptoge, Stephen; Caslake, Muriel; Thompson, Alexander; Butterworth, Adam S; Sarwar, Nadeem; Wormser, David; Saleheen, Danish; Ballantyne, Christie M; Psaty, Bruce M; et al. (JAMA, 2012)
CONTEXT: The value of assessing various emerging lipid-related markers for prediction of first cardiovascular events is debated. OBJECTIVE: To determine whether adding information on apolipoprotein B and apolipoprotein A-I, lipoprotein(a), or lipoprotein-associated phospholipase A2 to total cholesterol and high-density lipoprotein cholesterol (HDL-C) improves cardiovascular disease (CVD) risk prediction. DESIGN, SETTING, AND PARTICIPANTS: Individual records were available for 165,544 participants without baseline CVD in 37 prospective cohorts (calendar years of recruitment: 1968-2007) with up to 15,126 incident fatal or nonfatal CVD outcomes (10,132 CHD and 4994 stroke outcomes) during a median follow-up of 10.4 years (interquartile range, 7.6-14 years). MAIN OUTCOME MEASURES: Discrimination of CVD outcomes and reclassification of participants across predicted 10-year risk categories of low (<10%), intermediate (10%-<20%), and high (≥20%) risk. RESULTS: The addition of information on various lipid-related markers to total cholesterol, HDL-C, and other conventional risk factors yielded improvement in the model's discrimination: C-index change, 0.0006 (95% CI, 0.0002-0.0009) for the combination of apolipoprotein B and A-I; 0.0016 (95% CI, 0.0009-0.0023) for lipoprotein(a); and 0.0018 (95% CI, 0.0010-0.0026) for lipoprotein-associated phospholipase A2 mass. Net reclassification improvements were less than 1% with the addition of each of these markers to risk scores containing conventional risk factors. We estimated that for 100,000 adults aged 40 years or older, 15,436 would be initially classified at intermediate risk using conventional risk factors alone. Additional testing with a combination of apolipoprotein B and A-I would reclassify 1.1%; lipoprotein(a), 4.1%; and lipoprotein-associated phospholipase A2 mass, 2.7% of people to a 20% or higher predicted CVD risk category and, therefore, in need of statin treatment under Adult Treatment Panel III guidelines. CONCLUSION: In a study of individuals without known CVD, the addition of information on the combination of apolipoprotein B and A-I, lipoprotein(a), or lipoprotein-associated phospholipase A2 mass to risk scores containing total cholesterol and HDL-C led to slight improvement in CVD prediction.
Keywords: Aged; Biomarkers; Cardiovascular Diseases; Cholesterol, HDL; Cohort Studies; Female; Humans; Lipoproteins; Male; Middle Aged; Risk Assessment

Longitudinal changes in thyroid function in the oldest old and survival: the cardiovascular health study all-stars study. - Waring, Avantika C; Arnold, Alice M; Newman, Anne B; Bůzková, Petra; Hirsch, Calvin; Cappola, Anne R (J Clin Endocrinol Metab, 2012)
CONTEXT: Data on thyroid function in the oldest old are sparse, and existing studies show conflicting evidence on the relationship between thyroid function and mortality in this age group. OBJECTIVE: We describe longitudinal changes in thyroid function in a cohort of elderly individuals and determine the relationship between thyroid function and mortality. DESIGN, SETTING, AND PARTICIPANTS: Eight hundred forty-three participants in the Cardiovascular Health Study All Stars Study who were not taking thyroid medications and had thyroid function testing in 2005-2006 (mean age 85 yr). MAIN OUTCOME MEASURE: Thyroid-stimulating hormone (TSH), free T(4) (FT4), total T(3), and thyroid peroxidase antibody status were measured in 1992-1993 and 2005-2006. Deaths were ascertained through February 2011. RESULTS: There was a statistically significant 13% increase in TSH, 1.7% increase in FT4, and 13% decrease in total T(3) over the 13-yr period. Two hundred eighty-seven deaths occurred over a median follow-up of 5.1 yr. There was no association between subclinical hypothyroidism[hazard ratio (HR) 0.97, 95% confidence interval (CI) 0.66-1.43], TSH level (HR per milliunits per liter 0.94, 95% CI 0.88-1.01), or persistent thyroid peroxidase antibody positivity (HR 1.09, 95% CI 0.62-1.92), and death. However, FT4 was positively associated with death (HR per nanograms per deciliter 2.57, 95% CI 1.32-5.02). CONCLUSIONS: TSH increased over time in these older individuals. This elevation was not associated with increased or decreased mortality, although higher FT4 levels were associated with death. These findings raise concern for treatment of mild elevations of TSH in advanced age. Further studies are needed to determine the potential benefit of treating age-related changes in thyroid function.
Keywords: Aged, 80 and over; Female; Humans; Longitudinal Studies; Male; Thyroid Diseases; Thyroid Function Tests; Thyroid Gland; Thyrotropin; Thyroxine; Triiodothyronine

Meta-analyses identify 13 loci associated with age at menopause and highlight DNA repair and immune pathways. - Stolk, Lisette; Perry, John R B; Chasman, Daniel I; He, Chunyan; Mangino, Massimo; Sulem, Patrick; Barbalic, Maja; Broer, Linda; Byrne, Enda M; Ernst, Florian; Esko, Tõnu; Franceschini, Nora; et al. (Nat Genet, 2012)
To newly identify loci for age at natural menopause, we carried out a meta-analysis of 22 genome-wide association studies (GWAS) in 38,968 women of European descent, with replication in up to 14,435 women. In addition to four known loci, we identified 13 loci newly associated with age at natural menopause (at P < 5 × 10(-8)). Candidate genes located at these newly associated loci include genes implicated in DNA repair (EXO1, HELQ, UIMC1, FAM175A, FANCI, TLK1, POLG and PRIM1) and immune function (IL11, NLRP11 and PRRC2A (also known as BAT2)). Gene-set enrichment pathway analyses using the full GWAS data set identified exoDNase, NF-κB signaling and mitochondrial dysfunction as biological processes related to timing of menopause.
Keywords: Age Factors; DNA Helicases; DNA Polymerase gamma; DNA Primase; DNA Repair; DNA Repair Enzymes; DNA-Directed DNA Polymerase; European Continental Ancestry Group; Exodeoxyribonucleases; Female; Genetic Loci; Genome-Wide Association Study; Humans; Immunity; Menopause; Polymorphism, Single Nucleotide; Proteins

Meta-analysis identifies six new susceptibility loci for atrial fibrillation. - Ellinor, Patrick T; Lunetta, Kathryn L; Albert, Christine M; Glazer, Nicole L; Ritchie, Marylyn D; Smith, Albert V; Arking, Dan E; Müller-Nurasyid, Martina; Krijthe, Bouwe P; Lubitz, Steven A; Bis, Joshua C; Chung, Mina K; et al. (Nat Genet, 2012)
Atrial fibrillation is a highly prevalent arrhythmia and a major risk factor for stroke, heart failure and death. We conducted a genome-wide association study (GWAS) in individuals of European ancestry, including 6,707 with and 52,426 without atrial fibrillation. Six new atrial fibrillation susceptibility loci were identified and replicated in an additional sample of individuals of European ancestry, including 5,381 subjects with and 10,030 subjects without atrial fibrillation (P < 5 × 10(-8)). Four of the loci identified in Europeans were further replicated in silico in a GWAS of Japanese individuals, including 843 individuals with and 3,350 individuals without atrial fibrillation. The identified loci implicate candidate genes that encode transcription factors related to cardiopulmonary development, cardiac-expressed ion channels and cell signaling molecules.
Keywords: Adolescent; Adult; Aged; Aged, 80 and over; Asian Continental Ancestry Group; Atrial Fibrillation; Child; Child, Preschool; European Continental Ancestry Group; Female; Genetic Loci; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Infant; Infant, Newborn; Male; Middle Aged; Polymorphism, Single Nucleotide; Risk Factors; Young Adult

Multi-ethnic analysis of lipid-associated loci: the NHLBI CARe project. - Musunuru, Kiran; Romaine, Simon P R; Lettre, Guillaume; Wilson, James G; Volcik, Kelly A; Tsai, Michael Y; Taylor, Herman A; Schreiner, Pamela J; Rotter, Jerome I; Rich, Stephen S; Redline, Susan; Psaty, Bruce M; et al. (PLoS One, 2012)
BACKGROUND: Whereas it is well established that plasma lipid levels have substantial heritability within populations, it remains unclear how many of the genetic determinants reported in previous studies (largely performed in European American cohorts) are relevant in different ethnicities. METHODOLOGY/PRINCIPAL FINDINGS: We tested a set of ∼50,000 polymorphisms from ∼2,000 candidate genes and genetic loci from genome-wide association studies (GWAS) for association with low-density lipoprotein cholesterol (LDL-C), high-density lipoprotein cholesterol (HDL-C), and triglycerides (TG) in 25,000 European Americans and 9,000 African Americans in the National Heart, Lung, and Blood Institute (NHLBI) Candidate Gene Association Resource (CARe). We replicated associations for a number of genes in one or both ethnicities and identified a novel lipid-associated variant in a locus harboring ICAM1. We compared the architecture of genetic loci associated with lipids in both African Americans and European Americans and found that the same genes were relevant across ethnic groups but the specific associated variants at each gene often differed. CONCLUSIONS/SIGNIFICANCE: We identify or provide further evidence for a number of genetic determinants of plasma lipid levels through population association studies. In many loci the determinants appear to differ substantially between African Americans and European Americans.
Keywords: African Americans; Cholesterol, HDL; Cholesterol, LDL; European Continental Ancestry Group; Genetic Association Studies; Genetic Loci; Humans; Polymorphism, Single Nucleotide; Triglycerides

Novel loci associated with PR interval in a genome-wide association study of 10 African American cohorts. - Butler, Anne M; Yin, Xiaoyan; Evans, Daniel S; Nalls, Michael A; Smith, Erin N; Tanaka, Toshiko; Li, Guo; Buxbaum, Sarah G; Whitsel, Eric A; Alonso, Alvaro; Arking, Dan E; Benjamin, Emelia J; et al. (Circ Cardiovasc Genet, 2012)
BACKGROUND: The PR interval, as measured by the resting, standard 12-lead ECG, reflects the duration of atrial/atrioventricular nodal depolarization. Substantial evidence exists for a genetic contribution to PR, including genome-wide association studies that have identified common genetic variants at 9 loci influencing PR in populations of European and Asian descent. However, few studies have examined loci associated with PR in African Americans. METHODS AND RESULTS: We present results from the largest genome-wide association study to date of PR in 13 415 adults of African descent from 10 cohorts. We tested for association between PR (ms) and ≈2.8 million genotyped and imputed single-nucleotide polymorphisms. Imputation was performed using HapMap 2 YRI and CEU panels. Study-specific results, adjusted for global ancestry and clinical correlates of PR, were meta-analyzed using the inverse variance method. Variation in genome-wide test statistic distributions was noted within studies (λ range: 0.9-1.1), although not after genomic control correction was applied to the overall meta-analysis (λ: 1.008). In addition to generalizing previously reported associations with MEIS1, SCN5A, ARHGAP24, CAV1, and TBX5 to African American populations at the genome-wide significance level (P<5.0 × 10(-8)), we also identified a novel locus: ITGA9, located in a region previously implicated in SCN5A expression. The 3p21 region harboring SCN5A also contained 2 additional independent secondary signals influencing PR (P<5.0 × 10(-8)). CONCLUSIONS: This study demonstrates the ability to map novel loci in African Americans as well as the generalizability of loci associated with PR across populations of African, European, and Asian descent.
Keywords: Adult; African Americans; Cohort Studies; Electrocardiography; Female; Genetic Loci; Genome-Wide Association Study; Humans; Male; Meta-Analysis as Topic; Middle Aged; Polymorphism, Single Nucleotide

Novel loci for adiponectin levels and their influence on type 2 diabetes and metabolic traits: a multi-ethnic meta-analysis of 45,891 individuals. - Dastani, Zari; Hivert, Marie-France; Timpson, Nicholas; Perry, John R B; Yuan, Xin; Scott, Robert A; Henneman, Peter; Heid, Iris M; Kizer, Jorge R; Lyytikäinen, Leo-Pekka; Fuchsberger, Christian; Tanaka, Toshiko; et al. (PLoS Genet, 2012)
Circulating levels of adiponectin, a hormone produced predominantly by adipocytes, are highly heritable and are inversely associated with type 2 diabetes mellitus (T2D) and other metabolic traits. We conducted a meta-analysis of genome-wide association studies in 39,883 individuals of European ancestry to identify genes associated with metabolic disease. We identified 8 novel loci associated with adiponectin levels and confirmed 2 previously reported loci (P = 4.5×10(-8)-1.2×10(-43)). Using a novel method to combine data across ethnicities (N = 4,232 African Americans, N = 1,776 Asians, and N = 29,347 Europeans), we identified two additional novel loci. Expression analyses of 436 human adipocyte samples revealed that mRNA levels of 18 genes at candidate regions were associated with adiponectin concentrations after accounting for multiple testing (p<3×10(-4)). We next developed a multi-SNP genotypic risk score to test the association of adiponectin decreasing risk alleles on metabolic traits and diseases using consortia-level meta-analytic data. This risk score was associated with increased risk of T2D (p = 4.3×10(-3), n = 22,044), increased triglycerides (p = 2.6×10(-14), n = 93,440), increased waist-to-hip ratio (p = 1.8×10(-5), n = 77,167), increased glucose two hours post oral glucose tolerance testing (p = 4.4×10(-3), n = 15,234), increased fasting insulin (p = 0.015, n = 48,238), but with lower in HDL-cholesterol concentrations (p = 4.5×10(-13), n = 96,748) and decreased BMI (p = 1.4×10(-4), n = 121,335). These findings identify novel genetic determinants of adiponectin levels, which, taken together, influence risk of T2D and markers of insulin resistance.
Keywords: Adiponectin; African Americans; Asian Continental Ancestry Group; Cholesterol, HDL; Diabetes Mellitus, Type 2; European Continental Ancestry Group; Female; Gene Expression; Genetic Predisposition to Disease; Genome-Wide Association Study; Glucose Tolerance Test; Humans; Insulin Resistance; Male; Metabolic Networks and Pathways; Polymorphism, Single Nucleotide; Waist-Hip Ratio

Persistence and remission of musculoskeletal pain in community-dwelling older adults: results from the cardiovascular health study. - Thielke, Stephen M; Whitson, Heather; Diehr, Paula; O'Hare, Ann; Kearney, Patricia M; Chaudhry, Sarwat I; Zakai, Neil A; Kim, Dae; Sekaran, Nishant; Sale, Joanna E M; Arnold, Alice M; Chaves, Paulo; et al. (J Am Geriatr Soc, 2012)
OBJECTIVES: To characterize longitudinal patterns of musculoskeletal pain in a community sample of older adults over a 6-year period and to identify factors associated with persistence of pain. DESIGN: Secondary analysis of the Cardiovascular Health Study. SETTING: Community-based cohort drawn from four U.S. counties. PARTICIPANTS: Five thousand ninety-three men and women aged 65 and older. MEASUREMENTS: Over a 6-year period, pain was assessed each year using a single question about the presence of pain in any bones or joints during the last year. If affirmative, participants were queried about pain in seven locations (hands, shoulders, neck, back, hips, knees, feet). Participants were categorized according to the percentage of time that pain was present and according to the intermittent or chronic pattern of pain. Factors associated with persistent pain during five remaining years of the study were identified. RESULTS: Over 6 years, 32% of participants reported pain for three or more consecutive years, and 32% reported pain intermittently. Of those who reported pain the first year, 54% were pain free at least once during the follow-up period. Most of the pain at specific body locations was intermittent. Factors associated with remission of pain over 5 years included older age, male sex, better self-rated health, not being obese, taking fewer medications, and having fewer depressive symptoms. Approximately half of those with pain reported fewer pain locations the following year. CONCLUSION: Musculoskeletal pain in older adults, despite high prevalence, is often intermittent. The findings refute the notion that pain is an inevitable, unremitting, or progressive consequence of aging.
Keywords: Aged; Aged, 80 and over; Cardiovascular Diseases; Female; Humans; Male; Musculoskeletal Pain; Remission Induction; Residence Characteristics

A screening study of drug-drug interactions in cerivastatin users: an adverse effect of clopidogrel. - Floyd, J S; Kaspera, R; Marciante, K D; Weiss, N S; Heckbert, S R; Lumley, T; Wiggins, K L; Tamraz, B; Kwok, P-Y; Totah, R A; Psaty, B M (Clin Pharmacol Ther, 2012)
An analysis of a case-control study of rhabdomyolysis was conducted to screen for previously unrecognized cytochrome P450 enzyme (CYP) 2C8 inhibitors that may cause other clinically important drug-drug interactions. Medication use in cases of rhabdomyolysis using cerivastatin (n = 72) was compared with that in controls using atorvastatin (n = 287) for the period 1998-2001. The use of clopidogrel was strongly associated with rhabdomyolysis (odds ratio (OR) 29.6; 95% confidence interval (CI), 6.1-143). In a replication effort that used the US Food and Drug Administration (FDA) Adverse Event Reporting System (AERS), it was found that clopidogrel was used more commonly in patients with rhabdomyolysis receiving cerivastatin (17%) than in those receiving atorvastatin (0%, OR infinity; 95% CI = 5.2-infinity). Several medications were tested in vitro for their potential to cause drug-drug interactions. Clopidogrel, rosiglitazone, and montelukast were the most potent inhibitors of cerivastatin metabolism. Clopidogrel and its metabolites also inhibited cerivastatin metabolism in human hepatocytes. These epidemiological and in vitro findings suggest that clopidogrel may cause clinically important, dose-dependent drug-drug interactions with other medications metabolized by CYP2C8.
Keywords: Adverse Drug Reaction Reporting Systems; Aged; Aged, 80 and over; Aryl Hydrocarbon Hydroxylases; Case-Control Studies; Cytochrome P-450 CYP2C8; Cytochrome P-450 CYP3A; Cytochrome P-450 CYP3A Inhibitors; Drug Interactions; Female; Humans; Hydroxymethylglutaryl-CoA Reductase Inhibitors; Male; Platelet Aggregation Inhibitors; Pyridines; Rhabdomyolysis; Ticlopidine

Subclinical hyperthyroidism and the risk of coronary heart disease and mortality. - Collet, Tinh-Hai; Gussekloo, Jacobijn; Bauer, Douglas C; den Elzen, Wendy P J; Cappola, Anne R; Balmer, Philippe; Iervasi, Giorgio; Asvold, Bjørn O; Sgarbi, José A; Völzke, Henry; Gencer, Bariş; Maciel, Rui M B; et al. (Arch Intern Med, 2012)
BACKGROUND: Data from prospective cohort studies regarding the association between subclinical hyperthyroidism and cardiovascular outcomes are conflicting.We aimed to assess the risks of total and coronary heart disease (CHD) mortality, CHD events, and atrial fibrillation (AF) associated with endogenous subclinical hyperthyroidism among all available large prospective cohorts. METHODS: Individual data on 52 674 participants were pooled from 10 cohorts. Coronary heart disease events were analyzed in 22 437 participants from 6 cohorts with available data, and incident AF was analyzed in 8711 participants from 5 cohorts. Euthyroidism was defined as thyrotropin level between 0.45 and 4.49 mIU/L and endogenous subclinical hyperthyroidism as thyrotropin level lower than 0.45 mIU/L with normal free thyroxine levels, after excluding those receiving thyroid-altering medications. RESULTS: Of 52 674 participants, 2188 (4.2%) had subclinical hyperthyroidism. During follow-up, 8527 participants died (including 1896 from CHD), 3653 of 22 437 had CHD events, and 785 of 8711 developed AF. In age- and sex-adjusted analyses, subclinical hyperthyroidism was associated with increased total mortality (hazard ratio[HR], 1.24, 95% CI, 1.06-1.46), CHD mortality (HR,1.29; 95% CI, 1.02-1.62), CHD events (HR, 1.21; 95%CI, 0.99-1.46), and AF (HR, 1.68; 95% CI, 1.16-2.43).Risks did not differ significantly by age, sex, or preexisting cardiovascular disease and were similar after further adjustment for cardiovascular risk factors, with attributable risk of 14.5% for total mortality to 41.5% forAF in those with subclinical hyperthyroidism. Risks for CHD mortality and AF (but not other outcomes) were higher for thyrotropin level lower than 0.10 mIU/L compared with thyrotropin level between 0.10 and 0.44 mIU/L(for both, P value for trend, .03). CONCLUSION: Endogenous subclinical hyperthyroidism is associated with increased risks of total, CHD mortality, and incident AF, with highest risks of CHD mortality and AF when thyrotropin level is lower than 0.10 mIU/L.
Keywords: Adolescent; Adult; Age Distribution; Aged; Aged, 80 and over; Atrial Fibrillation; Cause of Death; Cohort Studies; Coronary Artery Disease; Female; Humans; Hyperthyroidism; Male; Middle Aged; Prognosis; Prospective Studies; Risk Assessment; Severity of Illness Index; Sex Distribution; Survival Analysis; Switzerland; Thyroid Function Tests; Thyrotropin; Young Adult

Subclinical thyroid dysfunction and the risk of heart failure events: an individual participant data analysis from 6 prospective cohorts. - Gencer, Bariş; Collet, Tinh-Hai; Virgini, Vanessa; Bauer, Douglas C; Gussekloo, Jacobijn; Cappola, Anne R; Nanchen, David; den Elzen, Wendy P J; Balmer, Philippe; Luben, Robert N; Iacoviello, Massimo; Triggiani, Vincenzo; et al. (Circulation, 2012)
BACKGROUND: American College of Cardiology/American Heart Association guidelines for the diagnosis and management of heart failure recommend investigating exacerbating conditions such as thyroid dysfunction, but without specifying the impact of different thyroid-stimulation hormone (TSH) levels. Limited prospective data exist on the association between subclinical thyroid dysfunction and heart failure events. METHODS AND RESULTS: We performed a pooled analysis of individual participant data using all available prospective cohorts with thyroid function tests and subsequent follow-up of heart failure events. Individual data on 25 390 participants with 216 248 person-years of follow-up were supplied from 6 prospective cohorts in the United States and Europe. Euthyroidism was defined as TSH of 0.45 to 4.49 mIU/L, subclinical hypothyroidism as TSH of 4.5 to 19.9 mIU/L, and subclinical hyperthyroidism as TSH <0.45 mIU/L, the last two with normal free thyroxine levels. Among 25 390 participants, 2068 (8.1%) had subclinical hypothyroidism and 648 (2.6%) had subclinical hyperthyroidism. In age- and sex-adjusted analyses, risks of heart failure events were increased with both higher and lower TSH levels (P for quadratic pattern <0.01); the hazard ratio was 1.01 (95% confidence interval, 0.81-1.26) for TSH of 4.5 to 6.9 mIU/L, 1.65 (95% confidence interval, 0.84-3.23) for TSH of 7.0 to 9.9 mIU/L, 1.86 (95% confidence interval, 1.27-2.72) for TSH of 10.0 to 19.9 mIU/L (P for trend <0.01) and 1.31 (95% confidence interval, 0.88-1.95) for TSH of 0.10 to 0.44 mIU/L and 1.94 (95% confidence interval, 1.01-3.72) for TSH <0.10 mIU/L (P for trend=0.047). Risks remained similar after adjustment for cardiovascular risk factors. CONCLUSION: Risks of heart failure events were increased with both higher and lower TSH levels, particularly for TSH ≥10 and <0.10 mIU/L.
Keywords: Adult; Aged; Aged, 80 and over; Comorbidity; Female; Follow-Up Studies; Heart Failure; Humans; Hypothyroidism; Male; Middle Aged; Prospective Studies; Risk; Risk Factors; Sensitivity and Specificity; Thyrotropin; Thyroxine

Ultraconserved elements in the human genome: association and transmission analyses of highly constrained single-nucleotide polymorphisms. - Chiang, Charleston W K; Liu, Ching-Ti; Lettre, Guillaume; Lange, Leslie A; Jorgensen, Neal W; Keating, Brendan J; Vedantam, Sailaja; Nock, Nora L; Franceschini, Nora; Reiner, Alex P; Demerath, Ellen W; Boerwinkle, Eric; et al. (Genetics, 2012)
Ultraconserved elements in the human genome likely harbor important biological functions as they are dosage sensitive and are able to direct tissue-specific expression. Because they are under purifying selection, variants in these elements may have a lower frequency in the population but a higher likelihood of association with complex traits. We tested a set of highly constrained SNPs (hcSNPs) distributed genome-wide among ultraconserved and nearly ultraconserved elements for association with seven traits related to reproductive (age at natural menopause, number of children, age at first child, and age at last child) and overall [longevity, body mass index (BMI), and height] fitness. Using up to 24,047 European-American samples from the National Heart, Lung, and Blood Institute Candidate Gene Association Resource (CARe), we observed an excess of associations with BMI and height. In an independent replication panel the most strongly associated SNPs showed an 8.4-fold enrichment of associations at the nominal level, including three variants in previously identified loci and one in a locus (DENND1A) previously shown to be associated with polycystic ovary syndrome. Finally, using 1430 family trios, we showed that the transmissions from heterozygous parents to offspring of the derived alleles of rare (frequency ≤ 0.5%) hcSNPs are not biased, particularly after adjusting for the rates of genotype missingness and error in the data. The lack of transmission bias ruled out an immediately and strongly deleterious effect due to the rare derived alleles, consistent with the observation that mice homozygous for the deletion of ultraconserved elements showed no overt phenotype. Our study also illustrated the importance of carefully modeling potential technical confounders when analyzing genotype data of rare variants.
Keywords: Alleles; Animals; Body Height; Body Mass Index; Child; Conserved Sequence; Dogs; Evolution, Molecular; Female; Genetic Fitness; Genetic Variation; Genome, Human; Genotype; Humans; Inheritance Patterns; Male; Mice; Pedigree; Phenotype; Polymorphism, Single Nucleotide; Rats; Reproduction; Young Adult

Use of stance time variability for predicting mobility disability in community-dwelling older persons: a prospective study. - Brach, Jennifer S; Wert, David; VanSwearingen, Jessie M; Newman, Anne B; Studenski, Stephanie A (J Geriatr Phys Ther, 2012)
BACKGROUND AND PURPOSE: Mobility disability is a serious and frequent adverse health outcome associated with aging. Early identification of individuals at risk for mobility disability is important if interventions to prevent disability are to be instituted. The objectives of this prospective study were to (1) determine the magnitude of stance time variability (STV) that discriminates individuals who currently have mobility disability (prevalent mobility disability) and (2) determine the magnitude of STV that predicts a new onset of mobility disability at 1 year (incident mobility disability). METHODS: A total of 552 community-dwelling older adults were evaluated as part of the Cardiovascular Health Study, a longitudinal cohort study. Stance time, in milliseconds, was determined from 2 passes on a 4-m computerized walkway at self-selected walking speed, and STV was defined as the standard deviation from approximately 12 individual steps. Mobility disability was defined as self-reported difficulty walking a one-half mile. Receiver operating characteristic (ROC) curves were plotted to determine an optimal cutoff value for STV for prevalent and incident mobility disability, and the area under the receiver operating characteristic curve (AUC) was computed. RESULTS: The optimal cutoff score for STV (maximizing sensitivity and specificity) for prevalent mobility disability was 0.037 seconds (sensitivity = 65%, specificity = 65%, AUC = 0.70) and for incident 1-year mobility disability was 0.034 seconds (sensitivity = 61%, specificity = 60%, AUC = 0.65). The use of likelihood ratios demonstrated a gradient of risk across values of STV, with mobility risk increasing as values of STV increased. DISCUSSION AND CONCLUSION: Values of STV may be useful in identifying older adults with mobility disability and at risk for future disability. We recommend the more conservative estimate for identifying risk, STV = 0.034 seconds, which maximizes the sensitivity and minimizes false negatives. The relatively modest values on the validity indices could possibly be improved by increasing the reliability of the measurement of STV. Clinicians should interpret the cutoff values liberally and use STV in conjunction with other measures until further work is completed to validate STV as an indicator of mobility disability.
Keywords: Aged; Aged, 80 and over; Disability Evaluation; Female; Gait; Geriatric Assessment; Humans; Independent Living; Male; Mobility Limitation; Physical Therapy Modalities; Postural Balance; Prospective Studies; Reproducibility of Results

Adhesion molecules, endothelin-1 and lung function in seven population-based cohorts. - Oelsner, E C; Pottinger, T D; Burkart, K M; Allison, M; Buxbaum, S G; Hansel, N N; Kumar, R; Larkin, E K; Lange, L A; Loehr, L R; London, S J; O'Connor, G T; et al. (Biomarkers, 2013)
CONTEXT: Endothelial function is abnormal in chronic obstructive pulmonary disease (COPD); whether endothelial dysfunction causes COPD is unknown. OBJECTIVE: Test associations of endothelial biomarkers with FEV1 using instrumental variables. METHODS: Among 26 907 participants with spirometry, ICAM-1, P-selectin, E-selectin and endothelin-1 were measured in subsets. RESULTS: ICAM-1 and P-selectin were inversely associated with FEV1 among European-Americans (-29 mL and -34 mL per standard deviation of log-transformed biomarker, p < 0.001), as was endothelin-1 among African-Americans (-22 mL, p = 0.008). Genetically-estimated ICAM-1 and P-selectin were not significantly associated with FEV1. The instrumental variable for endothelin-1 was non-informative. CONCLUSION: Although ICAM-1, P-selectin and endothelin-1 were inversely associated with FEV1, associations for ICAM-1 and P-selectin do not appear causal.
Keywords: African Continental Ancestry Group; Biomarkers; Cohort Studies; E-Selectin; Endothelin-1; Endothelium, Vascular; European Continental Ancestry Group; Female; Gene Expression; Humans; Intercellular Adhesion Molecule-1; Lung; Male; Middle Aged; P-Selectin; Pulmonary Disease, Chronic Obstructive; Respiratory Function Tests; Spirometry

Association of heat shock proteins with all-cause mortality. - Broer, L; Demerath, E W; Garcia, M E; Homuth, G; Kaplan, R C; Lunetta, K L; Tanaka, T; Tranah, G J; Walter, S; Arnold, A M; Atzmon, G; Harris, T B; et al. (Age (Dordr), 2013)
Experimental mild heat shock is widely known as an intervention that results in extended longevity in various models along the evolutionary lineage. Heat shock proteins (HSPs) are highly upregulated immediately after a heat shock. The elevation in HSP levels was shown to inhibit stress-mediated cell death, and recent experiments indicate a highly versatile role for these proteins as inhibitors of programmed cell death. In this study, we examined common genetic variations in 31 genes encoding all members of the HSP70, small HSP, and heat shock factor (HSF) families for their association with all-cause mortality. Our discovery cohort was the Rotterdam study (RS1) containing 5,974 participants aged 55 years and older (3,174 deaths). We assessed 4,430 single nucleotide polymorphisms (SNPs) using the HumanHap550K Genotyping BeadChip from Illumina. After adjusting for multiple testing by permutation analysis, three SNPs showed evidence for association with all-cause mortality in RS1. These findings were followed in eight independent population-based cohorts, leading to a total of 25,007 participants (8,444 deaths). In the replication phase, only HSF2 (rs1416733) remained significantly associated with all-cause mortality. Rs1416733 is a known cis-eQTL for HSF2. Our findings suggest a role of HSF2 in all-cause mortality.
Keywords: Aged, 80 and over; Aging; Cause of Death; Forecasting; Genotype; Heat-Shock Proteins; Humans; Longevity; Promoter Regions, Genetic; Retrospective Studies; Transcription, Genetic; United States

Best practices and joint calling of the HumanExome BeadChip: the CHARGE Consortium. - Grove, Megan L; Yu, Bing; Cochran, Barbara J; Haritunians, Talin; Bis, Joshua C; Taylor, Kent D; Hansen, Mark; Borecki, Ingrid B; Cupples, L Adrienne; Fornage, Myriam; Gudnason, Vilmundur; Harris, Tamara B; et al. (PLoS One, 2013)
Genotyping arrays are a cost effective approach when typing previously-identified genetic polymorphisms in large numbers of samples. One limitation of genotyping arrays with rare variants (e.g., minor allele frequency [MAF] <0.01) is the difficulty that automated clustering algorithms have to accurately detect and assign genotype calls. Combining intensity data from large numbers of samples may increase the ability to accurately call the genotypes of rare variants. Approximately 62,000 ethnically diverse samples from eleven Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) Consortium cohorts were genotyped with the Illumina HumanExome BeadChip across seven genotyping centers. The raw data files for the samples were assembled into a single project for joint calling. To assess the quality of the joint calling, concordance of genotypes in a subset of individuals having both exome chip and exome sequence data was analyzed. After exclusion of low performing SNPs on the exome chip and non-overlap of SNPs derived from sequence data, genotypes of 185,119 variants (11,356 were monomorphic) were compared in 530 individuals that had whole exome sequence data. A total of 98,113,070 pairs of genotypes were tested and 99.77% were concordant, 0.14% had missing data, and 0.09% were discordant. We report that joint calling allows the ability to accurately genotype rare variation using array technology when large sample sizes are available and best practices are followed. The cluster file from this experiment is available at www.chargeconsortium.com/main/exomechip.
Keywords: Aging; Alleles; Cluster Analysis; Cohort Studies; Continental Population Groups; Exome; Female; Gene Frequency; Genomics; Genotype; Heart; Humans; Male; Oligonucleotide Array Sequence Analysis; Polymorphism, Single Nucleotide; Sample Size; Self Report; Sequence Analysis, DNA

Bidirectional relationship between cognitive function and pneumonia. - Shah, Faraaz Ali; Pike, Francis; Alvarez, Karina; Angus, Derek; Newman, Anne B; Lopez, Oscar; Tate, Judith; Kapur, Vishesh; Wilsdon, Anthony; Krishnan, Jerry A; Hansel, Nadia; Au, David; et al. (Am J Respir Crit Care Med, 2013)
RATIONALE: Relationships between chronic health conditions and acute infections remain poorly understood. Preclinical studies suggest crosstalk between nervous and immune systems. OBJECTIVES: To determine bidirectional relationships between cognition and pneumonia. METHODS: We conducted longitudinal analyses of a population-based cohort over 10 years. We determined whether changes in cognition increase risk of pneumonia hospitalization by trajectory analyses and joint modeling. We then determined whether pneumonia hospitalization increased risk of subsequent dementia using a Cox model with pneumonia as a time-varying covariate. MEASUREMENTS AND MAIN RESULTS: Of the 5,888 participants, 639 (10.9%) were hospitalized with pneumonia at least once. Most participants had normal cognition before pneumonia. Three cognition trajectories were identified: no, minimal, and severe rapid decline. A greater proportion of participants hospitalized with pneumonia were on trajectories of minimal or severe decline before occurrence of pneumonia compared with those never hospitalized with pneumonia (proportion with no, minimal, and severe decline were 67.1%, 22.8%, and 10.0% vs. 76.0%, 19.3%, and 4.6% for participants with and without pneumonia, respectively; P < 0.001). Small subclinical changes in cognition increased risk of pneumonia, even in those with normal cognition and physical function before pneumonia (β = -0.02; P < 0.001). Participants with pneumonia were subsequently at an increased risk of dementia (hazard ratio, 2.24 [95% confidence interval, 1.62-3.11]; P = 0.01). Associations were independent of demographics, health behaviors, other chronic conditions, and physical function. Bidirectional relationship did not vary based on severity of disease, and similar associations were noted for those with severe sepsis and other infections. CONCLUSIONS: A bidirectional relationship exists between pneumonia and cognition and may explain how a single episode of infection in well-appearing older individuals accelerates decline in chronic health conditions and loss of functional independence.
Keywords: Aged; Cognition Disorders; Dementia; Female; Hospitalization; Humans; Longitudinal Studies; Male; Neuropsychological Tests; Pneumonia; Proportional Hazards Models; Risk Factors

Blood pressure variability and the risk of all-cause mortality, incident myocardial infarction, and incident stroke in the cardiovascular health study. - Suchy-Dicey, Astrid M; Wallace, Erin R; Mitchell, S V Elkind; Aguilar, Maria; Gottesman, Rebecca F; Rice, Kenneth; Kronmal, Richard; Psaty, Bruce M; Longstreth, W T (Am J Hypertens, 2013)
BACKGROUND: Recent reports have linked variability in visit-to-visit systolic blood pressure (SBP) to risk of mortality and stroke, independent of the effect of mean SBP level. This study aimed to evaluate whether variability in SBP is associated with all-cause mortality, incident myocardial infarction (MI), and incident stroke, independent of mean SBP or trends in SBP levels over time. METHODS: The Cardiovascular Health Study is a longitudinal cohort study of vascular risk factors and disease in the elderly. Participants who attended their first 5 annual clinic visits and experienced no event before the 5th visit were eligible (n = 3,852). Primary analyses were restricted to participants not using antihypertensive medications throughout the first 5 clinic visits (n = 1,642). Intraindividual SBP variables were defined using each participant's 5-visit blood pressure measures. Cox proportional hazards models estimated adjusted hazard ratios (HRs) per SD increase in intraindividual SBP variability, adjusted for intraindividual SBP mean and change over time. RESULTS: Over a mean follow-up of 9.9 years, there were 844 deaths, 203 MIs, and 195 strokes. Intraindividual SBP variability was significantly associated with increased risk of mortality (HR = 1.13; 95% confidence interval (CI) = 1.05-1.21) and of incident MI (HR = 1.20; 95%CI = 1.06-1.36), independent of the effect from adjustment factors. Intraindividual SBP variability was not associated with risk of stroke (HR = 1.03; 95% CI = 0.89-1.21). CONCLUSIONS: Long-term visit-to-visit SBP variability was independently associated with a higher risk of subsequent mortality and MI but not stroke. More research is needed to determine the relationship of BP variability with cardiovascular risk and the clinical implications.
Keywords: Aged; Blood Pressure; Cohort Studies; Female; Humans; Incidence; Longitudinal Studies; Male; Mortality; Myocardial Infarction; Risk; Stroke; United States

Common carotid intima-media thickness does not add to Framingham risk score in individuals with diabetes mellitus: the USE-IMT initiative. - den Ruijter, H M; Peters, S A E; Groenewegen, K A; Anderson, T J; Britton, A R; Dekker, J M; Engstrom, G; Eijkemans, M J; Evans, G W; de Graaf, J; Grobbee, D E; Hedblad, B; et al. (Diabetologia, 2013)
AIMS/HYPOTHESIS: The aim of this work was to investigate whether measurement of the mean common carotid intima-media thickness (CIMT) improves cardiovascular risk prediction in individuals with diabetes. METHODS: We performed a subanalysis among 4,220 individuals with diabetes in a large ongoing individual participant data meta-analysis involving 56,194 subjects from 17 population-based cohorts worldwide. We first refitted the risk factors of the Framingham heart risk score on the individuals without previous cardiovascular disease (baseline model) and then expanded this model with the mean common CIMT (CIMT model). The absolute 10 year risk for developing a myocardial infarction or stroke was estimated from both models. In individuals with diabetes we compared discrimination and calibration of the two models. Reclassification of individuals with diabetes was based on allocation to another cardiovascular risk category when mean common CIMT was added. RESULTS: During a median follow-up of 8.7 years, 684 first-time cardiovascular events occurred among the population with diabetes. The C statistic was 0.67 for the Framingham model and 0.68 for the CIMT model. The absolute 10 year risk for developing a myocardial infarction or stroke was 16% in both models. There was no net reclassification improvement with the addition of mean common CIMT (1.7%; 95% CI -1.8, 3.8). There were no differences in the results between men and women. CONCLUSIONS/INTERPRETATION: There is no improvement in risk prediction in individuals with diabetes when measurement of the mean common CIMT is added to the Framingham risk score. Therefore, this measurement is not recommended for improving individual cardiovascular risk stratification in individuals with diabetes.
Keywords: Cardiovascular Diseases; Carotid Intima-Media Thickness; Diabetes Mellitus; Humans; Myocardial Infarction; Risk Factors; Stroke

Common FABP4 genetic variants and plasma levels of fatty acid binding protein 4 in older adults. - Mukamal, Kenneth J; Wilk, Jemma B; Biggs, Mary L; Jensen, Majken K; Ix, Joachim H; Kizer, Jorge R; Tracy, Russell P; Zieman, Susan J; Mozaffarian, Dariush; Psaty, Bruce M; Siscovick, David S; Djoussé, Luc (Lipids, 2013)
We examined common variants in the fatty acid binding protein 4 gene (FABP4) and plasma levels of FABP4 in adults aged 65 and older from the Cardiovascular Health Study. We genotyped rs16909187, rs1054135, rs16909192, rs10808846, rs7018409, rs2290201, and rs6992708 and measured circulating FABP4 levels among 3190 European Americans and 660 African Americans. Among European Americans, the minor alleles of six single nucleotide polymorphisms (SNP) were associated with lower FABP4 levels (all p ≤ 0.01). Among African Americans, the SNP with the lowest minor allele frequency was associated with lower FABP4 levels (p = 0.015). The C-A haplotype of rs16909192 and rs2290201 was associated with lower FABP4 levels in both European Americans (frequency = 16 %; p = 0.001) and African Americans (frequency = 8 %; p = 0.04). The haplotype combined a SNP in the first intron with one in the 3'untranslated region. However, the alleles associated with lower FABP4 levels were associated with higher fasting glucose in meta-analyses from the MAGIC consortium. These results demonstrate associations of common SNP and haplotypes in the FABP4 gene with lower plasma FABP4 but higher fasting glucose levels.
Keywords: African Americans; Aged; Aged, 80 and over; Blood Glucose; Body Mass Index; Cohort Studies; European Continental Ancestry Group; Fatty Acid-Binding Proteins; Female; Gene Frequency; Genetic Association Studies; Haplotypes; Humans; Insulin; Linkage Disequilibrium; Male; Polymorphism, Single Nucleotide

Common genetic loci influencing plasma homocysteine concentrations and their effect on risk of coronary artery disease. - van Meurs, Joyce B J; Paré, Guillaume; Schwartz, Stephen M; Hazra, Aditi; Tanaka, Toshiko; Vermeulen, Sita H; Cotlarciuc, Ioana; Yuan, Xin; Mälarstig, Anders; Bandinelli, Stefania; Bis, Joshua C; Blom, Henk; et al. (Am J Clin Nutr, 2013)
BACKGROUND: The strong observational association between total homocysteine (tHcy) concentrations and risk of coronary artery disease (CAD) and the null associations in the homocysteine-lowering trials have prompted the need to identify genetic variants associated with homocysteine concentrations and risk of CAD. OBJECTIVE: We tested whether common genetic polymorphisms associated with variation in tHcy are also associated with CAD. DESIGN: We conducted a meta-analysis of genome-wide association studies (GWAS) on tHcy concentrations in 44,147 individuals of European descent. Polymorphisms associated with tHcy (P < 10(⁻⁸) were tested for association with CAD in 31,400 cases and 92,927 controls. RESULTS: Common variants at 13 loci, explaining 5.9% of the variation in tHcy, were associated with tHcy concentrations, including 6 novel loci in or near MMACHC (2.1 × 10⁻⁹), SLC17A3 (1.0 × 10⁻⁸), GTPB10 (1.7 × 10⁻⁸), CUBN (7.5 × 10⁻¹⁰), HNF1A (1.2 × 10⁻¹²)), and FUT2 (6.6 × 10⁻⁹), and variants previously reported at or near the MTHFR, MTR, CPS1, MUT, NOX4, DPEP1, and CBS genes. Individuals within the highest 10% of the genotype risk score (GRS) had 3-μmol/L higher mean tHcy concentrations than did those within the lowest 10% of the GRS (P = 1 × 10⁻³⁶). The GRS was not associated with risk of CAD (OR: 1.01; 95% CI: 0.98, 1.04; P = 0.49). CONCLUSIONS: We identified several novel loci that influence plasma tHcy concentrations. Overall, common genetic variants that influence plasma tHcy concentrations are not associated with risk of CAD in white populations, which further refutes the causal relevance of moderately elevated tHcy concentrations and tHcy-related pathways for CAD.
Keywords: Coronary Artery Disease; Genes; Genetic Loci; Genetic Predisposition to Disease; Genotype; Homocysteine; Humans; Polymorphism, Genetic; Risk Factors

Common genetic variation near the connexin-43 gene is associated with resting heart rate in African Americans: a genome-wide association study of 13,372 participants. - Deo, R; Nalls, M A; Avery, C L; Smith, J G; Evans, D S; Keller, M F; Butler, A M; Buxbaum, S G; Li, G; Miguel Quibrera, P; Smith, E N; Tanaka, T; et al. (Heart Rhythm, 2013)
BACKGROUND: Genome-wide association studies have identified several genetic loci associated with variation in resting heart rate in European and Asian populations. No study has evaluated genetic variants associated with heart rate in African Americans. OBJECTIVE: To identify novel genetic variants associated with resting heart rate in African Americans. METHODS: Ten cohort studies participating in the Candidate-gene Association Resource and Continental Origins and Genetic Epidemiology Network consortia performed genome-wide genotyping of single nucleotide polymorphisms (SNPs) and imputed 2,954,965 SNPs using HapMap YRI and CEU panels in 13,372 participants of African ancestry. Each study measured the RR interval (ms) from 10-second resting 12-lead electrocardiograms and estimated RR-SNP associations using covariate-adjusted linear regression. Random-effects meta-analysis was used to combine cohort-specific measures of association and identify genome-wide significant loci (P≤2.5×10(-8)). RESULTS: Fourteen SNPs on chromosome 6q22 exceeded the genome-wide significance threshold. The most significant association was for rs9320841 (+13 ms per minor allele; P = 4.98×10(-15)). This SNP was approximately 350 kb downstream of GJA1, a locus previously identified as harboring SNPs associated with heart rate in Europeans. Adjustment for rs9320841 also attenuated the association between the remaining 13 SNPs in this region and heart rate. In addition, SNPs in MYH6, which have been identified in European genome-wide association study, were associated with similar changes in the resting heart rate as this population of African Americans. CONCLUSIONS: An intergenic region downstream of GJA1 (the gene encoding connexin 43, the major protein of the human myocardial gap junction) and an intragenic region within MYH6 are associated with variation in resting heart rate in African Americans as well as in populations of European and Asian origin.
Keywords: Adult; African Americans; Aged; Arrhythmias, Cardiac; Connexin 43; Electrocardiography; Female; Genetic Variation; Genome-Wide Association Study; Genotype; Heart Rate; Humans; Male; Meta-Analysis as Topic; Middle Aged; Polymorphism, Single Nucleotide; Rest; United States

Common variants associated with plasma triglycerides and risk for coronary artery disease. - Do, Ron; Willer, Cristen J; Schmidt, Ellen M; Sengupta, Sebanti; Gao, Chi; Peloso, Gina M; Gustafsson, Stefan; Kanoni, Stavroula; Ganna, Andrea; Chen, Jin; Buchkovich, Martin L; Mora, Samia; et al. (Nat Genet, 2013)
Triglycerides are transported in plasma by specific triglyceride-rich lipoproteins; in epidemiological studies, increased triglyceride levels correlate with higher risk for coronary artery disease (CAD). However, it is unclear whether this association reflects causal processes. We used 185 common variants recently mapped for plasma lipids (P < 5 × 10(-8) for each) to examine the role of triglycerides in risk for CAD. First, we highlight loci associated with both low-density lipoprotein cholesterol (LDL-C) and triglyceride levels, and we show that the direction and magnitude of the associations with both traits are factors in determining CAD risk. Second, we consider loci with only a strong association with triglycerides and show that these loci are also associated with CAD. Finally, in a model accounting for effects on LDL-C and/or high-density lipoprotein cholesterol (HDL-C) levels, the strength of a polymorphism's effect on triglyceride levels is correlated with the magnitude of its effect on CAD risk. These results suggest that triglyceride-rich lipoproteins causally influence risk for CAD.
Keywords: Biological Transport; Cholesterol, HDL; Cholesterol, LDL; Coronary Artery Disease; Humans; Polymorphism, Single Nucleotide; Risk Factors; Triglycerides

Common variants in Mendelian kidney disease genes and their association with renal function. - Parsa, Afshin; Fuchsberger, Christian; Köttgen, Anna; O'Seaghdha, Conall M; Pattaro, Cristian; de Andrade, Mariza; Chasman, Daniel I; Teumer, Alexander; Endlich, Karlhans; Olden, Matthias; Chen, Ming-Huei; Tin, Adrienne; et al. (J Am Soc Nephrol, 2013)
Many common genetic variants identified by genome-wide association studies for complex traits map to genes previously linked to rare inherited Mendelian disorders. A systematic analysis of common single-nucleotide polymorphisms (SNPs) in genes responsible for Mendelian diseases with kidney phenotypes has not been performed. We thus developed a comprehensive database of genes for Mendelian kidney conditions and evaluated the association between common genetic variants within these genes and kidney function in the general population. Using the Online Mendelian Inheritance in Man database, we identified 731 unique disease entries related to specific renal search terms and confirmed a kidney phenotype in 218 of these entries, corresponding to mutations in 258 genes. We interrogated common SNPs (minor allele frequency >5%) within these genes for association with the estimated GFR in 74,354 European-ancestry participants from the CKDGen Consortium. However, the top four candidate SNPs (rs6433115 at LRP2, rs1050700 at TSC1, rs249942 at PALB2, and rs9827843 at ROBO2) did not achieve significance in a stage 2 meta-analysis performed in 56,246 additional independent individuals, indicating that these common SNPs are not associated with estimated GFR. The effect of less common or rare variants in these genes on kidney function in the general population and disease-specific cohorts requires further research.
Keywords: Databases, Genetic; European Continental Ancestry Group; Gene Frequency; Genetic Variation; Genome-Wide Association Study; Humans; Kidney; Mendelian Randomization Analysis; Phenotype; Polymorphism, Single Nucleotide; Renal Insufficiency, Chronic

Discovery and refinement of loci associated with lipid levels. - Willer, Cristen J; Schmidt, Ellen M; Sengupta, Sebanti; Peloso, Gina M; Gustafsson, Stefan; Kanoni, Stavroula; Ganna, Andrea; Chen, Jin; Buchkovich, Martin L; Mora, Samia; Beckmann, Jacques S; Bragg-Gresham, Jennifer L; et al. (Nat Genet, 2013)
Levels of low-density lipoprotein (LDL) cholesterol, high-density lipoprotein (HDL) cholesterol, triglycerides and total cholesterol are heritable, modifiable risk factors for coronary artery disease. To identify new loci and refine known loci influencing these lipids, we examined 188,577 individuals using genome-wide and custom genotyping arrays. We identify and annotate 157 loci associated with lipid levels at P < 5 × 10(-8), including 62 loci not previously associated with lipid levels in humans. Using dense genotyping in individuals of European, East Asian, South Asian and African ancestry, we narrow association signals in 12 loci. We find that loci associated with blood lipid levels are often associated with cardiovascular and metabolic traits, including coronary artery disease, type 2 diabetes, blood pressure, waist-hip ratio and body mass index. Our results demonstrate the value of using genetic data from individuals of diverse ancestry and provide insights into the biological mechanisms regulating blood lipids to guide future genetic, biological and therapeutic research.
Keywords: African Continental Ancestry Group; Asian Continental Ancestry Group; Cholesterol, HDL; Cholesterol, LDL; Coronary Artery Disease; European Continental Ancestry Group; Genetic Predisposition to Disease; Genome-Wide Association Study; Genotype; Humans; Lipids; Triglycerides

Effects of respiratory and non-respiratory factors on disability among older adults with airway obstruction: the Cardiovascular Health Study. - Locke, Emily; Thielke, Stephen; Diehr, Paula; Wilsdon, Anthony G; Barr, R Graham; Hansel, Nadia; Kapur, Vishesh K; Krishnan, Jerry; Enright, Paul; Heckbert, Susan R; Kronmal, Richard A; Fan, Vincent S (COPD, 2013)
BACKGROUND: High rates of disability associated with chronic airway obstruction may be caused by impaired pulmonary function, pulmonary symptoms, other chronic diseases, or systemic inflammation. METHODS: We analyzed data from the Cardiovascular Health Study, a longitudinal cohort of 5888 older adults. Categories of lung function (normal; restricted; borderline, mild-moderate, and severe obstruction) were delineated by baseline spirometry (without bronchodilator). Disability-free years were calculated as total years alive and without self-report of difficulty performing &γτ;1 Instrumental Activities of Daily Living over 6 years of follow-up. Using linear regression, we compared disability-free years by lung disease category, adjusting for demographic factors, body mass index, smoking, cognition, and other chronic co-morbidities. Among participants with airflow obstruction, we examined the association of respiratory factors (FEV1 and dyspnea) and non-respiratory factors (ischemic heart disease, congestive heart failure, diabetes, muscle weakness, osteoporosis, depression and cognitive impairment) on disability-free years. RESULTS: The average disability free years were 4.0 out of a possible 6 years. Severe obstruction was associated with 1 fewer disability-free year compared to normal spirometry in the adjusted model. For the 1,048 participants with airway obstruction, both respiratory factors (FEV1 and dyspnea) and non-respiratory factors (heart disease, coronary artery disease, diabetes, depression, osteoporosis, cognitive function, and weakness) were associated with decreased disability-free years. CONCLUSIONS: Severe obstruction is associated with greater disability compared to patients with normal spirometery. Both respiratory and non-respiratory factors contribute to disability in older adults with abnormal spirometry.
Keywords: Activities of Daily Living; Aged; Cognition Disorders; Cohort Studies; Comorbidity; Depression; Diabetes Mellitus; Disease Progression; Dyspnea; Female; Heart Failure; Humans; Linear Models; Longitudinal Studies; Male; Muscle Weakness; Myocardial Ischemia; Osteoporosis; Pulmonary Disease, Chronic Obstructive; Severity of Illness Index; Spirometry

Effects of smoking on the genetic risk of obesity: the population architecture using genomics and epidemiology study. - Fesinmeyer, Megan D; North, Kari E; Lim, Unhee; Bůzková, Petra; Crawford, Dana C; Haessler, Jeffrey; Gross, Myron D; Fowke, Jay H; Goodloe, Robert; Love, Shelley-Ann; Graff, Misa; Carlson, Christopher S; et al. (BMC Med Genet, 2013)
BACKGROUND: Although smoking behavior is known to affect body mass index (BMI), the potential for smoking to influence genetic associations with BMI is largely unexplored. METHODS: As part of the 'Population Architecture using Genomics and Epidemiology (PAGE)' Consortium, we investigated interaction between genetic risk factors associated with BMI and smoking for 10 single nucleotide polymorphisms (SNPs) previously identified in genome-wide association studies. We included 6 studies with a total of 56,466 subjects (16,750 African Americans (AA) and 39,716 European Americans (EA)). We assessed effect modification by testing an interaction term for each SNP and smoking (current vs. former/never) in the linear regression and by stratified analyses. RESULTS: We did not observe strong evidence for interactions and only observed two interactions with p-values <0.1: for rs6548238/TMEM18, the risk allele (C) was associated with BMI only among AA females who were former/never smokers (β = 0.018, p = 0.002), vs. current smokers (β = 0.001, p = 0.95, p(interaction) = 0.10). For rs9939609/FTO, the A allele was more strongly associated with BMI among current smoker EA females (β = 0.017, p = 3.5 x 10(-5)), vs. former/never smokers (β = 0.006, p = 0.05, p(interaction) = 0.08). CONCLUSIONS: These analyses provide limited evidence that smoking status may modify genetic effects of previously identified genetic risk factors for BMI. Larger studies are needed to follow up our results. CLINICAL TRIAL REGISTRATION: NCT00000611.
Keywords: Adolescent; Adult; African Americans; Aged; Alpha-Ketoglutarate-Dependent Dioxygenase FTO; Body Mass Index; European Continental Ancestry Group; Female; Genetic Predisposition to Disease; Humans; Male; Membrane Proteins; Middle Aged; Obesity; Polymorphism, Single Nucleotide; Proteins; Risk Factors; Smoking; Young Adult

Epidemiology and long-term clinical and biologic risk factors for pneumonia in community-dwelling older Americans: analysis of three cohorts. - Yende, Sachin; Alvarez, Karina; Loehr, Laura; Folsom, Aaron R; Newman, Anne B; Weissfeld, Lisa A; Wunderink, Richard G; Kritchevsky, Stephen B; Mukamal, Kenneth J; London, Stephanie J; Harris, Tamara B; Bauer, Doug C; et al. (Chest, 2013)
BACKGROUND: Preventing pneumonia requires better understanding of incidence, mortality, and long-term clinical and biologic risk factors, particularly in younger individuals. METHODS: This was a cohort study in three population-based cohorts of community-dwelling individuals. A derivation cohort (n = 16,260) was used to determine incidence and survival and develop a risk prediction model. The prediction model was validated in two cohorts (n = 8,495). The primary outcome was 10-year risk of pneumonia hospitalization. RESULTS: The crude and age-adjusted incidences of pneumonia were 6.71 and 9.43 cases/1,000 person-years (10-year risk was 6.15%). The 30-day and 1-year mortality were 16.5% and 31.5%. Although age was the most important risk factor (range of crude incidence rates, 1.69-39.13 cases/1,000 person-years for each 5-year increment from 45-85 years), 38% of pneumonia cases occurred in adults < 65 years of age. The 30-day and 1-year mortality were 12.5% and 25.7% in those < 65 years of age. Although most comorbidities were associated with higher risk of pneumonia, reduced lung function was the most important risk factor (relative risk = 6.61 for severe reduction based on FEV1 by spirometry). A clinical risk prediction model based on age, smoking, and lung function predicted 10-year risk (area under curve [AUC] = 0.77 and Hosmer-Lemeshow [HL] C statistic = 0.12). Model discrimination and calibration were similar in the internal validation cohort (AUC = 0.77; HL C statistic, 0.65) but lower in the external validation cohort (AUC = 0.62; HL C statistic, 0.45). The model also calibrated well in blacks and younger adults. C-reactive protein and IL-6 were associated with higher pneumonia risk but did not improve model performance. CONCLUSIONS: Pneumonia hospitalization is common and associated with high mortality, even in younger healthy adults. Long-term risk of pneumonia can be predicted in community-dwelling adults with a simple clinical risk prediction model.
Keywords: Age Factors; Aged; Aged, 80 and over; Community-Acquired Infections; Comorbidity; Female; Follow-Up Studies; Hospitalization; Humans; Incidence; Male; Middle Aged; Pneumonia; Prognosis; Prospective Studies; Risk Assessment; Risk Factors; Survival Rate; Time Factors

Evaluating subject-level incremental values of new markers for risk classification rule. - Cai, T; Tian, L; Lloyd-Jones, D; Wei, L J (Lifetime Data Anal, 2013)
Suppose that we need to classify a population of subjects into several well-defined ordered risk categories for disease prevention or management with their "baseline" risk factors/markers. In this article, we present a systematic approach to identify subjects using their conventional risk factors/markers who would benefit from a new set of risk markers for more accurate classification. Specifically for each subgroup of individuals with the same conventional risk estimate, we present inference procedures for the reclassification and the corresponding correct re-categorization rates with the new markers. We then apply these new tools to analyze the data from the Cardiovascular Health Study sponsored by the US National Heart, Lung, and Blood Institute. We used Framingham risk factors plus the information of baseline anti-hypertensive drug usage to identify adult American women who may benefit from the measurement of a new blood biomarker, CRP, for better risk classification in order to intensify prevention of coronary heart disease for the subsequent 10 years.
Keywords: Aged; Antihypertensive Agents; Biomarkers; Biostatistics; C-Reactive Protein; Confidence Intervals; Coronary Disease; Female; Humans; Risk; Risk Factors; Statistics, Nonparametric; United States

Fine Mapping and Identification of BMI Loci in African Americans. - Gong, Jian; Schumacher, Fredrick; Lim, Unhee; Hindorff, Lucia A; Haessler, Jeff; Buyske, Steven; Carlson, Christopher S; Rosse, Stephanie; Bůzková, Petra; Fornage, Myriam; Gross, Myron; Pankratz, Nathan; et al. (Am J Hum Genet, 2013)
Genome-wide association studies (GWASs) primarily performed in European-ancestry (EA) populations have identified numerous loci associated with body mass index (BMI). However, it is still unclear whether these GWAS loci can be generalized to other ethnic groups, such as African Americans (AAs). Furthermore, the putative functional variant or variants in these loci mostly remain under investigation. The overall lower linkage disequilibrium in AA compared to EA populations provides the opportunity to narrow in or fine-map these BMI-related loci. Therefore, we used the Metabochip to densely genotype and evaluate 21 BMI GWAS loci identified in EA studies in 29,151 AAs from the Population Architecture using Genomics and Epidemiology (PAGE) study. Eight of the 21 loci (SEC16B, TMEM18, ETV5, GNPDA2, TFAP2B, BDNF, FTO, and MC4R) were found to be associated with BMI in AAs at 5.8 × 10(-5). Within seven out of these eight loci, we found that, on average, a substantially smaller number of variants was correlated (r(2) > 0.5) with the most significant SNP in AA than in EA populations (16 versus 55). Conditional analyses revealed GNPDA2 harboring a potential additional independent signal. Moreover, Metabochip-wide discovery analyses revealed two BMI-related loci, BRE (rs116612809, p = 3.6 × 10(-8)) and DHX34 (rs4802349, p = 1.2 × 10(-7)), which were significant when adjustment was made for the total number of SNPs tested across the chip. These results demonstrate that fine mapping in AAs is a powerful approach for both narrowing in on the underlying causal variants in known loci and discovering BMI-related loci.
Keywords: Adult; African Americans; Aged; Aged, 80 and over; Body Mass Index; Female; Genetic Loci; Genetic Predisposition to Disease; Genome, Human; Genome-Wide Association Study; Genotype; Humans; Linkage Disequilibrium; Male; Middle Aged; Obesity; Polymorphism, Single Nucleotide; Young Adult

Genetic analysis of a population heavy drinking phenotype identifies risk variants in whites. - Hamidovic, Ajna; Goodloe, Robert J; Young, Taylor R; Styn, Mindi A; Mukamal, Kenneth J; Choquet, Helene; Kasberger, Jay L; Buxbaum, Sarah G; Papanicolaou, George J; White, Wendy; Volcik, Kelly; Spring, Bonnie; et al. (J Clin Psychopharmacol, 2013)
Genetic association studies thus far have used detailed diagnoses of alcoholism to identify loci associated with risk. This proof-of-concept analysis examined whether population data of lifetime heaviest alcohol consumption may be used to identify genetic loci that modulate risk. We conducted a genetic association study in European Americans between variants in approximately 2100 genes and alcohol consumption as part of the Candidate gene Association Resource project. We defined cases as individuals with a history of drinking 5 or more drinks per day almost every day of the week and controls as current light drinkers (1-5 drinks per week). We cross-validated identified single nucleotide polymorphisms in a meta-analysis of 2 cohorts of unrelated individuals--Atherosclerosis Risk in Communities (ARIC) and Cardiovascular Health Study (CHS)--and in a separate cohort of related individuals--Framingham Heart Study (FHS). The most significant variant in the meta-analysis of ARIC and CHS was rs6933598 in methylenetetrahydrofolate dehydrogenase (P = 7.46 × 10(-05)) with a P value in FHS of 0.042. The top variants in FHS were rs12249562 in cubulin (P = 3.03 × 10(-05)) and rs9839267 near cholecystokinin (P = 3.05 × 10(-05)) with a P value of 0.019 for rs9839267 in CHS. We have here shown feasibility in evaluating lifetime incidence of heavy alcohol drinking from population-based studies for the purpose of conducting genetic association analyses.
Keywords: Aged; Alcohol Drinking; Alcoholism; Case-Control Studies; European Continental Ancestry Group; Feasibility Studies; Genetic Association Studies; Genetic Loci; Genetic Predisposition to Disease; Genetic Variation; Humans; Incidence; Male; Middle Aged; Phenotype; Polymorphism, Single Nucleotide; Risk

Genetic loci for retinal arteriolar microcirculation. - Sim, Xueling; Jensen, Richard A; Ikram, M Kamran; Cotch, Mary Frances; Li, Xiaohui; Macgregor, Stuart; Xie, Jing; Smith, Albert Vernon; Boerwinkle, Eric; Mitchell, Paul; Klein, Ronald; Klein, Barbara E K; et al. (PLoS One, 2013)
Narrow arterioles in the retina have been shown to predict hypertension as well as other vascular diseases, likely through an increase in the peripheral resistance of the microcirculatory flow. In this study, we performed a genome-wide association study in 18,722 unrelated individuals of European ancestry from the Cohorts for Heart and Aging Research in Genomic Epidemiology consortium and the Blue Mountain Eye Study, to identify genetic determinants associated with variations in retinal arteriolar caliber. Retinal vascular calibers were measured on digitized retinal photographs using a standardized protocol. One variant (rs2194025 on chromosome 5q14 near the myocyte enhancer factor 2C MEF2C gene) was associated with retinal arteriolar caliber in the meta-analysis of the discovery cohorts at genome-wide significance of P-value <5×10(-8). This variant was replicated in an additional 3,939 individuals of European ancestry from the Australian Twins Study and Multi-Ethnic Study of Atherosclerosis (rs2194025, P-value = 2.11×10(-12) in combined meta-analysis of discovery and replication cohorts). In independent studies of modest sample sizes, no significant association was found between this variant and clinical outcomes including coronary artery disease, stroke, myocardial infarction or hypertension. In conclusion, we found one novel loci which underlie genetic variation in microvasculature which may be relevant to vascular disease. The relevance of these findings to clinical outcomes remains to be determined.
Keywords: Aged; Aged, 80 and over; Arterioles; Chromosomes, Human, Pair 5; European Continental Ancestry Group; Female; Genetic Loci; Genome-Wide Association Study; Genotype; Humans; Male; MEF2 Transcription Factors; Microcirculation; Middle Aged; Models, Genetic; Retinal Vessels

Genetic risk factors for BMI and obesity in an ethnically diverse population: results from the population architecture using genomics and epidemiology (PAGE) study. - Fesinmeyer, Megan D; North, Kari E; Ritchie, Marylyn D; Lim, Unhee; Franceschini, Nora; Wilkens, Lynne R; Gross, Myron D; Bůzková, Petra; Glenn, Kimberly; Quibrera, P Miguel; Fernandez-Rhodes, Lindsay; Li, Qiong; et al. (Obesity (Silver Spring), 2013)
OBJECTIVE: Several genome-wide association studies (GWAS) have demonstrated that common genetic variants contribute to obesity. However, studies of this complex trait have focused on ancestrally European populations, despite the high prevalence of obesity in some minority groups. DESIGN AND METHODS: As part of the "Population Architecture using Genomics and Epidemiology (PAGE)" Consortium, we investigated the association between 13 GWAS-identified single-nucleotide polymorphisms (SNPs) and BMI and obesity in 69,775 subjects, including 6,149 American Indians, 15,415 African-Americans, 2,438 East Asians, 7,346 Hispanics, 604 Pacific Islanders, and 37,823 European Americans. For the BMI-increasing allele of each SNP, we calculated β coefficients using linear regression (for BMI) and risk estimates using logistic regression (for obesity defined as BMI ≥ 30) followed by fixed-effects meta-analysis to combine results across PAGE sites. Analyses stratified by racial/ethnic group assumed an additive genetic model and were adjusted for age, sex, and current smoking. We defined "replicating SNPs" (in European Americans) and "generalizing SNPs" (in other racial/ethnic groups) as those associated with an allele frequency-specific increase in BMI. RESULTS: By this definition, we replicated 9/13 SNP associations (5 out of 8 loci) in European Americans. We also generalized 8/13 SNP associations (5/8 loci) in East Asians, 7/13 (5/8 loci) in African Americans, 6/13 (4/8 loci) in Hispanics, 5/8 in Pacific Islanders (5/8 loci), and 5/9 (4/8 loci) in American Indians. CONCLUSION: Linkage disequilibrium patterns suggest that tagSNPs selected for European Americans may not adequately tag causal variants in other ancestry groups. Accordingly, fine-mapping in large samples is needed to comprehensively explore these loci in diverse populations.
Keywords: Alleles; Body Mass Index; Ethnic Groups; Gene Frequency; Genetic Loci; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Linkage Disequilibrium; Metagenomics; Obesity; Phenotype; Polymorphism, Single Nucleotide; Risk Factors

Genetic variants associated with fasting glucose and insulin concentrations in an ethnically diverse population: results from the Population Architecture using Genomics and Epidemiology (PAGE) study. - Fesinmeyer, Megan D; Meigs, James B; North, Kari E; Schumacher, Fredrick R; Bůzková, Petra; Franceschini, Nora; Haessler, Jeffrey; Goodloe, Robert; Spencer, Kylee L; Voruganti, Venkata Saroja; Howard, Barbara V; Jackson, Rebecca; et al. (BMC Med Genet, 2013)
BACKGROUND: Multiple genome-wide association studies (GWAS) within European populations have implicated common genetic variants associated with insulin and glucose concentrations. In contrast, few studies have been conducted within minority groups, which carry the highest burden of impaired glucose homeostasis and type 2 diabetes in the U.S. METHODS: As part of the 'Population Architecture using Genomics and Epidemiology (PAGE) Consortium, we investigated the association of up to 10 GWAS-identified single nucleotide polymorphisms (SNPs) in 8 genetic regions with glucose or insulin concentrations in up to 36,579 non-diabetic subjects including 23,323 European Americans (EA) and 7,526 African Americans (AA), 3,140 Hispanics, 1,779 American Indians (AI), and 811 Asians. We estimated the association between each SNP and fasting glucose or log-transformed fasting insulin, followed by meta-analysis to combine results across PAGE sites. RESULTS: Overall, our results show that 9/9 GWAS SNPs are associated with glucose in EA (p = 0.04 to 9 × 10-15), versus 3/9 in AA (p= 0.03 to 6 × 10-5), 3/4 SNPs in Hispanics, 2/4 SNPs in AI, and 1/2 SNPs in Asians. For insulin we observed a significant association with rs780094/GCKR in EA, Hispanics and AI only. CONCLUSIONS: Generalization of results across multiple racial/ethnic groups helps confirm the relevance of some of these loci for glucose and insulin metabolism. Lack of association in non-EA groups may be due to insufficient power, or to unique patterns of linkage disequilibrium.
Keywords: Adaptor Proteins, Signal Transducing; Adult; African Americans; Aged; Alleles; Asian Continental Ancestry Group; Blood Glucose; Diabetes Mellitus, Type 2; European Continental Ancestry Group; Female; Gene Frequency; Genetic Loci; Genome-Wide Association Study; Genomics; Hispanic Americans; Humans; Indians, North American; Insulin; Male; Middle Aged; Polymorphism, Single Nucleotide; Transcription Factor 7-Like 2 Protein

Genome-wide and gene-centric analyses of circulating myeloperoxidase levels in the charge and care consortia. - Reiner, Alexander P; Hartiala, Jaana; Zeller, Tanja; Bis, Joshua C; Dupuis, Josée; Fornage, Myriam; Baumert, Jens; Kleber, Marcus E; Wild, Philipp S; Baldus, Stephan; Bielinski, Suzette J; Fontes, João D; et al. (Hum Mol Genet, 2013)
Increased systemic levels of myeloperoxidase (MPO) are associated with the risk of coronary artery disease (CAD). To identify the genetic factors that are associated with circulating MPO levels, we carried out a genome-wide association study (GWAS) and a gene-centric analysis in subjects of European ancestry and African Americans (AAs). A locus on chromosome 1q31.1 containing the complement factor H (CFH) gene was strongly associated with serum MPO levels in 9305 subjects of European ancestry (lead SNP rs800292; P = 4.89 × 10(-41)) and in 1690 AA subjects (rs505102; P = 1.05 × 10(-8)). Gene-centric analyses in 8335 subjects of European ancestry additionally identified two rare MPO coding sequence variants that were associated with serum MPO levels (rs28730837, P = 5.21 × 10(-12); rs35897051, P = 3.32 × 10(-8)). A GWAS for plasma MPO levels in 9260 European ancestry subjects identified a chromosome 17q22 region near MPO that was significantly associated (lead SNP rs6503905; P = 2.94 × 10(-12)), but the CFH locus did not exhibit evidence of association with plasma MPO levels. Functional analyses revealed that rs800292 was associated with levels of complement proteins in serum. Variants at chromosome 17q22 also had pleiotropic cis effects on gene expression. In a case-control analysis of ∼80 000 subjects from CARDIoGRAM, none of the identified single-nucleotide polymorphisms (SNPs) were associated with CAD. These results suggest that distinct genetic factors regulate serum and plasma MPO levels, which may have relevance for various acute and chronic inflammatory disorders. The clinical implications for CAD and a better understanding of the functional basis for the association of CFH and MPO variants with circulating MPO levels require further study.
Keywords: Adult; African Americans; Aged; Case-Control Studies; Complement Factor H; Coronary Artery Disease; European Continental Ancestry Group; Female; Gene Expression Regulation, Enzymologic; Genetic Association Studies; Genetic Variation; Genome-Wide Association Study; Genotype; Humans; Male; Middle Aged; Peroxidase; Polymorphism, Single Nucleotide; Young Adult

Genome-wide association analyses identify 18 new loci associated with serum urate concentrations. - Köttgen, Anna; Albrecht, Eva; Teumer, Alexander; Vitart, Veronique; Krumsiek, Jan; Hundertmark, Claudia; Pistis, Giorgio; Ruggiero, Daniela; O'Seaghdha, Conall M; Haller, Toomas; Yang, Qiong; Tanaka, Toshiko; et al. (Nat Genet, 2013)
Elevated serum urate concentrations can cause gout, a prevalent and painful inflammatory arthritis. By combining data from >140,000 individuals of European ancestry within the Global Urate Genetics Consortium (GUGC), we identified and replicated 28 genome-wide significant loci in association with serum urate concentrations (18 new regions in or near TRIM46, INHBB, SFMBT1, TMEM171, VEGFA, BAZ1B, PRKAG2, STC1, HNF4G, A1CF, ATXN2, UBE2Q2, IGF1R, NFAT5, MAF, HLF, ACVR1B-ACVRL1 and B3GNT4). Associations for many of the loci were of similar magnitude in individuals of non-European ancestry. We further characterized these loci for associations with gout, transcript expression and the fractional excretion of urate. Network analyses implicate the inhibins-activins signaling pathways and glucose metabolism in systemic urate control. New candidate genes for serum urate concentration highlight the importance of metabolic control of urate production and excretion, which may have implications for the treatment and prevention of gout.
Keywords: Analysis of Variance; European Continental Ancestry Group; Gene Frequency; Genetic Loci; Genome-Wide Association Study; Glucose; Gout; Humans; Inhibins; Polymorphism, Single Nucleotide; Signal Transduction; Uric Acid

Genome-wide association of body fat distribution in African ancestry populations suggests new loci. - Liu, Ching-Ti; Monda, Keri L; Taylor, Kira C; Lange, Leslie; Demerath, Ellen W; Palmas, Walter; Wojczynski, Mary K; Ellis, Jaclyn C; Vitolins, Mara Z; Liu, Simin; Papanicolaou, George J; Irvin, Marguerite R; et al. (PLoS Genet, 2013)
Central obesity, measured by waist circumference (WC) or waist-hip ratio (WHR), is a marker of body fat distribution. Although obesity disproportionately affects minority populations, few studies have conducted genome-wide association study (GWAS) of fat distribution among those of predominantly African ancestry (AA). We performed GWAS of WC and WHR, adjusted and unadjusted for BMI, in up to 33,591 and 27,350 AA individuals, respectively. We identified loci associated with fat distribution in AA individuals using meta-analyses of GWA results for WC and WHR (stage 1). Overall, 25 SNPs with single genomic control (GC)-corrected p-values<5.0 × 10(-6) were followed-up (stage 2) in AA with WC and with WHR. Additionally, we interrogated genomic regions of previously identified European ancestry (EA) WHR loci among AA. In joint analysis of association results including both Stage 1 and 2 cohorts, 2 SNPs demonstrated association, rs2075064 at LHX2, p = 2.24×10(-8) for WC-adjusted-for-BMI, and rs6931262 at RREB1, p = 2.48×10(-8) for WHR-adjusted-for-BMI. However, neither signal was genome-wide significant after double GC-correction (LHX2: p = 6.5 × 10(-8); RREB1: p = 5.7 × 10(-8)). Six of fourteen previously reported loci for waist in EA populations were significant (p<0.05 divided by the number of independent SNPs within the region) in AA studied here (TBX15-WARS2, GRB14, ADAMTS9, LY86, RSPO3, ITPR2-SSPN). Further, we observed associations with metabolic traits: rs13389219 at GRB14 associated with HDL-cholesterol, triglycerides, and fasting insulin, and rs13060013 at ADAMTS9 with HDL-cholesterol and fasting insulin. Finally, we observed nominal evidence for sexual dimorphism, with stronger results in AA women at the GRB14 locus (p for interaction = 0.02). In conclusion, we identified two suggestive loci associated with fat distribution in AA populations in addition to confirming 6 loci previously identified in populations of EA. These findings reinforce the concept that there are fat distribution loci that are independent of generalized adiposity.
Keywords: Adiposity; African Continental Ancestry Group; Body Fat Distribution; European Continental Ancestry Group; Female; Genetic Loci; Genome-Wide Association Study; Humans; Male; Obesity; Polymorphism, Single Nucleotide; Waist-Hip Ratio

A genome-wide association study for venous thromboembolism: the extended cohorts for heart and aging research in genomic epidemiology (CHARGE) consortium. - Tang, Weihong; Teichert, Martina; Chasman, Daniel I; Heit, John A; Morange, Pierre-Emmanuel; Li, Guo; Pankratz, Nathan; Leebeek, Frank W; Paré, Guillaume; de Andrade, Mariza; Tzourio, Christophe; Psaty, Bruce M; et al. (Genet Epidemiol, 2013)
Venous thromboembolism (VTE) is a common, heritable disease resulting in high rates of hospitalization and mortality. Yet few associations between VTE and genetic variants, all in the coagulation pathway, have been established. To identify additional genetic determinants of VTE, we conducted a two-stage genome-wide association study (GWAS) among individuals of European ancestry in the extended cohorts for heart and aging research in genomic epidemiology (CHARGE) VTE consortium. The discovery GWAS comprised 1,618 incident VTE cases out of 44,499 participants from six community-based studies. Genotypes for genome-wide single-nucleotide polymorphisms (SNPs) were imputed to approximately 2.5 million SNPs in HapMap and association with VTE assessed using study-design appropriate regression methods. Meta-analysis of these results identified two known loci, in F5 and ABO. Top 1,047 tag SNPs (P ≤ 0.0016) from the discovery GWAS were tested for association in an additional 3,231 cases and 3,536 controls from three case-control studies. In the combined data from these two stages, additional genome-wide significant associations were observed on 4q35 at F11 (top SNP rs4253399, intronic to F11) and on 4q28 at FGG (rs6536024, 9.7 kb from FGG; P < 5.0 × 10(-13) for both). The associations at the FGG locus were not completely explained by previously reported variants. Loci at or near SUSD1 and OTUD7A showed borderline yet novel associations (P < 5.0 × 10(-6) ) and constitute new candidate genes. In conclusion, this large GWAS replicated key genetic associations in F5 and ABO, and confirmed the importance of F11 and FGG loci for VTE. Future studies are warranted to better characterize the associations with F11 and FGG and to replicate the new candidate associations.
Keywords: Aged; Aging; Case-Control Studies; Cohort Studies; Female; Genome-Wide Association Study; Humans; Male; Meta-Analysis as Topic; Middle Aged; Polymorphism, Single Nucleotide; Regression Analysis; Risk Factors; Venous Thromboembolism

A genome-wide association study of depressive symptoms. - Hek, Karin; Demirkan, Ayse; Lahti, Jari; Terracciano, Antonio; Teumer, Alexander; Cornelis, Marilyn C; Amin, Najaf; Bakshis, Erin; Baumert, Jens; Ding, Jingzhong; Liu, Yongmei; Marciante, Kristin; et al. (Biol Psychiatry, 2013)
BACKGROUND: Depression is a heritable trait that exists on a continuum of varying severity and duration. Yet, the search for genetic variants associated with depression has had few successes. We exploit the entire continuum of depression to find common variants for depressive symptoms. METHODS: In this genome-wide association study, we combined the results of 17 population-based studies assessing depressive symptoms with the Center for Epidemiological Studies Depression Scale. Replication of the independent top hits (p<1×10(-5)) was performed in five studies assessing depressive symptoms with other instruments. In addition, we performed a combined meta-analysis of all 22 discovery and replication studies. RESULTS: The discovery sample comprised 34,549 individuals (mean age of 66.5) and no loci reached genome-wide significance (lowest p = 1.05×10(-7)). Seven independent single nucleotide polymorphisms were considered for replication. In the replication set (n = 16,709), we found suggestive association of one single nucleotide polymorphism with depressive symptoms (rs161645, 5q21, p = 9.19×10(-3)). This 5q21 region reached genome-wide significance (p = 4.78×10(-8)) in the overall meta-analysis combining discovery and replication studies (n = 51,258). CONCLUSIONS: The results suggest that only a large sample comprising more than 50,000 subjects may be sufficiently powered to detect genes for depressive symptoms.
Keywords: Aged; Aged, 80 and over; Chromosomes, Human, Pair 5; Depression; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Male; Middle Aged; Polymorphism, Single Nucleotide

A genome-wide association study of early menopause and the combined impact of identified variants. - Perry, John R B; Corre, Tanguy; Esko, Tõnu; Chasman, Daniel I; Fischer, Krista; Franceschini, Nora; He, Chunyan; Kutalik, Zoltán; Mangino, Massimo; Rose, Lynda M; Vernon Smith, Albert; Stolk, Lisette; et al. (Hum Mol Genet, 2013)
Early menopause (EM) affects up to 10% of the female population, reducing reproductive lifespan considerably. Currently, it constitutes the leading cause of infertility in the western world, affecting mainly those women who postpone their first pregnancy beyond the age of 30 years. The genetic aetiology of EM is largely unknown in the majority of cases. We have undertaken a meta-analysis of genome-wide association studies (GWASs) in 3493 EM cases and 13 598 controls from 10 independent studies. No novel genetic variants were discovered, but the 17 variants previously associated with normal age at natural menopause as a quantitative trait (QT) were also associated with EM and primary ovarian insufficiency (POI). Thus, EM has a genetic aetiology which overlaps variation in normal age at menopause and is at least partly explained by the additive effects of the same polygenic variants. The combined effect of the common variants captured by the single nucleotide polymorphism arrays was estimated to account for ∼30% of the variance in EM. The association between the combined 17 variants and the risk of EM was greater than the best validated non-genetic risk factor, smoking.
Keywords: Case-Control Studies; Female; Gene Frequency; Genome-Wide Association Study; Humans; Menopause, Premature; Polymorphism, Single Nucleotide; Primary Ovarian Insufficiency; Quantitative Trait Loci; Risk

Genome-wide association study of retinopathy in individuals without diabetes. - Jensen, Richard A; Sim, Xueling; Li, Xiaohui; Cotch, Mary Frances; Ikram, M Kamran; Holliday, Elizabeth G; Eiriksdottir, Gudny; Harris, Tamara B; Jonasson, Fridbert; Klein, Barbara E K; Launer, Lenore J; Smith, Albert Vernon; et al. (PLoS One, 2013)
BACKGROUND: Mild retinopathy (microaneurysms or dot-blot hemorrhages) is observed in persons without diabetes or hypertension and may reflect microvascular disease in other organs. We conducted a genome-wide association study (GWAS) of mild retinopathy in persons without diabetes. METHODS: A working group agreed on phenotype harmonization, covariate selection and analytic plans for within-cohort GWAS. An inverse-variance weighted fixed effects meta-analysis was performed with GWAS results from six cohorts of 19,411 Caucasians. The primary analysis included individuals without diabetes and secondary analyses were stratified by hypertension status. We also singled out the results from single nucleotide polymorphisms (SNPs) previously shown to be associated with diabetes and hypertension, the two most common causes of retinopathy. RESULTS: No SNPs reached genome-wide significance in the primary analysis or the secondary analysis of participants with hypertension. SNP, rs12155400, in the histone deacetylase 9 gene (HDAC9) on chromosome 7, was associated with retinopathy in analysis of participants without hypertension, -1.3±0.23 (beta ± standard error), p = 6.6×10(-9). Evidence suggests this was a false positive finding. The minor allele frequency was low (∼2%), the quality of the imputation was moderate (r(2) ∼0.7), and no other common variants in the HDAC9 gene were associated with the outcome. SNPs found to be associated with diabetes and hypertension in other GWAS were not associated with retinopathy in persons without diabetes or in subgroups with or without hypertension. CONCLUSIONS: This GWAS of retinopathy in individuals without diabetes showed little evidence of genetic associations. Further studies are needed to identify genes associated with these signs in order to help unravel novel pathways and determinants of microvascular diseases.
Keywords: Aged; Aged, 80 and over; Female; Genome-Wide Association Study; Genotype; Histone Deacetylases; Humans; Hypertension; Male; Polymorphism, Single Nucleotide; Repressor Proteins; Retinal Diseases

Genome-wide meta-analysis identifies 11 new loci for anthropometric traits and provides insights into genetic architecture. - Berndt, Sonja I; Gustafsson, Stefan; Mägi, Reedik; Ganna, Andrea; Wheeler, Eleanor; Feitosa, Mary F; Justice, Anne E; Monda, Keri L; Croteau-Chonka, Damien C; Day, Felix R; Esko, Tõnu; Fall, Tove; et al. (Nat Genet, 2013)
Approaches exploiting trait distribution extremes may be used to identify loci associated with common traits, but it is unknown whether these loci are generalizable to the broader population. In a genome-wide search for loci associated with the upper versus the lower 5th percentiles of body mass index, height and waist-to-hip ratio, as well as clinical classes of obesity, including up to 263,407 individuals of European ancestry, we identified 4 new loci (IGFBP4, H6PD, RSRC1 and PPP2R2A) influencing height detected in the distribution tails and 7 new loci (HNF4G, RPTOR, GNAT2, MRPS33P4, ADCY9, HS6ST3 and ZZZ3) for clinical classes of obesity. Further, we find a large overlap in genetic structure and the distribution of variants between traits based on extremes and the general population and little etiological heterogeneity between obesity subgroups.
Keywords: Anthropometry; Body Height; Body Mass Index; Case-Control Studies; European Continental Ancestry Group; Genetic Predisposition to Disease; Genome-Wide Association Study; Genotype; Humans; Meta-Analysis as Topic; Obesity; Phenotype; Polymorphism, Single Nucleotide; Quantitative Trait Loci; Waist-Hip Ratio

Genome-wide meta-analysis of observational studies shows common genetic variants associated with macronutrient intake. - Tanaka, Toshiko; Ngwa, Julius S; van Rooij, Frank J A; Zillikens, M Carola; Wojczynski, Mary K; Frazier-Wood, Alexis C; Houston, Denise K; Kanoni, Stavroula; Lemaitre, Rozenn N; Luan, Jian'an; Mikkilä, Vera; Renstrom, Frida; et al. (Am J Clin Nutr, 2013)
BACKGROUND: Macronutrient intake varies substantially between individuals, and there is evidence that this variation is partly accounted for by genetic variants. OBJECTIVE: The objective of the study was to identify common genetic variants that are associated with macronutrient intake. DESIGN: We performed 2-stage genome-wide association (GWA) meta-analysis of macronutrient intake in populations of European descent. Macronutrients were assessed by using food-frequency questionnaires and analyzed as percentages of total energy consumption from total fat, protein, and carbohydrate. From the discovery GWA (n = 38,360), 35 independent loci associated with macronutrient intake at P < 5 × 10(-6) were identified and taken forward to replication in 3 additional cohorts (n = 33,533) from the DietGen Consortium. For one locus, fat mass obesity-associated protein (FTO), cohorts with Illumina MetaboChip genotype data (n = 7724) provided additional replication data. RESULTS: A variant in the chromosome 19 locus (rs838145) was associated with higher carbohydrate (β ± SE: 0.25 ± 0.04%; P = 1.68 × 10(-8)) and lower fat (β ± SE: -0.21 ± 0.04%; P = 1.57 × 10(-9)) consumption. A candidate gene in this region, fibroblast growth factor 21 (FGF21), encodes a fibroblast growth factor involved in glucose and lipid metabolism. The variants in this locus were associated with circulating FGF21 protein concentrations (P < 0.05) but not mRNA concentrations in blood or brain. The body mass index (BMI)-increasing allele of the FTO variant (rs1421085) was associated with higher protein intake (β ± SE: 0.10 ± 0.02%; P = 9.96 × 10(-10)), independent of BMI (after adjustment for BMI, β ± SE: 0.08 ± 0.02%; P = 3.15 × 10(-7)). CONCLUSION: Our results indicate that variants in genes involved in nutrient metabolism and obesity are associated with macronutrient consumption in humans. Trials related to this study were registered at clinicaltrials.gov as NCT00005131 (Atherosclerosis Risk in Communities), NCT00005133 (Cardiovascular Health Study), NCT00005136 (Family Heart Study), NCT00005121 (Framingham Heart Study), NCT00083369 (Genetic and Environmental Determinants of Triglycerides), NCT01331512 (InCHIANTI Study), and NCT00005487 (Multi-Ethnic Study of Atherosclerosis).
Keywords: Alleles; Atherosclerosis; Body Mass Index; Dietary Carbohydrates; Dietary Fats; Dietary Proteins; Energy Intake; European Continental Ancestry Group; Fibroblast Growth Factors; Follow-Up Studies; Gene-Environment Interaction; Genetic Predisposition to Disease; Genome-Wide Association Study; Genotype; Humans; Life Style; Obesity; Polymorphism, Single Nucleotide; Prospective Studies; Quantitative Trait Loci; Surveys and Questionnaires

Genome-wide study identifies two loci associated with lung function decline in mild to moderate COPD. - Hansel, Nadia N; Ruczinski, Ingo; Rafaels, Nicholas; Sin, Don D; Daley, Denise; Malinina, Alla; Huang, Lili; Sandford, Andrew; Murray, Tanda; Kim, Yoonhee; Vergara, Candelaria; Heckbert, Susan R; et al. (Hum Genet, 2013)
Accelerated lung function decline is a key COPD phenotype; however, its genetic control remains largely unknown. We performed a genome-wide association study using the Illumina Human660W-Quad v.1_A BeadChip. Generalized estimation equations were used to assess genetic contributions to lung function decline over a 5-year period in 4,048 European American Lung Health Study participants with largely mild COPD. Genotype imputation was performed using reference HapMap II data. To validate regions meeting genome-wide significance, replication of top SNPs was attempted in independent cohorts. Three genes (TMEM26, ANK3 and FOXA1) within the regions of interest were selected for tissue expression studies using immunohistochemistry. Two intergenic SNPs (rs10761570, rs7911302) on chromosome 10 and one SNP on chromosome 14 (rs177852) met genome-wide significance after Bonferroni. Further support for the chromosome 10 region was obtained by imputation, the most significantly associated imputed SNPs (rs10761571, rs7896712) being flanked by observed markers rs10761570 and rs7911302. Results were not replicated in four general population cohorts or a smaller cohort of subjects with moderate to severe COPD; however, we show novel expression of genes near regions of significantly associated SNPS, including TMEM26 and FOXA1 in airway epithelium and lung parenchyma, and ANK3 in alveolar macrophages. Levels of expression were associated with lung function and COPD status. We identified two novel regions associated with lung function decline in mild COPD. Genes within these regions were expressed in relevant lung cells and their expression related to airflow limitation suggesting they may represent novel candidate genes for COPD susceptibility.
Keywords: Adult; Ankyrins; Chromosomes, Human, Pair 10; Chromosomes, Human, Pair 14; Cohort Studies; Female; Genome-Wide Association Study; Hepatocyte Nuclear Factor 3-alpha; Humans; Linkage Disequilibrium; Lung; Male; Membrane Proteins; Middle Aged; Polymorphism, Single Nucleotide; Pulmonary Disease, Chronic Obstructive

Higher magnesium intake is associated with lower fasting glucose and insulin, with no evidence of interaction with select genetic loci, in a meta-analysis of 15 CHARGE Consortium Studies. - Hruby, Adela; Ngwa, Julius S; Renstrom, Frida; Wojczynski, Mary K; Ganna, Andrea; Hallmans, Göran; Houston, Denise K; Jacques, Paul F; Kanoni, Stavroula; Lehtimäki, Terho; Lemaitre, Rozenn N; Manichaikul, Ani; et al. (J Nutr, 2013)
Favorable associations between magnesium intake and glycemic traits, such as fasting glucose and insulin, are observed in observational and clinical studies, but whether genetic variation affects these associations is largely unknown. We hypothesized that single nucleotide polymorphisms (SNPs) associated with either glycemic traits or magnesium metabolism affect the association between magnesium intake and fasting glucose and insulin. Fifteen studies from the CHARGE (Cohorts for Heart and Aging Research in Genomic Epidemiology) Consortium provided data from up to 52,684 participants of European descent without known diabetes. In fixed-effects meta-analyses, we quantified 1) cross-sectional associations of dietary magnesium intake with fasting glucose (mmol/L) and insulin (ln-pmol/L) and 2) interactions between magnesium intake and SNPs related to fasting glucose (16 SNPs), insulin (2 SNPs), or magnesium (8 SNPs) on fasting glucose and insulin. After adjustment for age, sex, energy intake, BMI, and behavioral risk factors, magnesium (per 50-mg/d increment) was inversely associated with fasting glucose [β = -0.009 mmol/L (95% CI: -0.013, -0.005), P < 0.0001] and insulin [-0.020 ln-pmol/L (95% CI: -0.024, -0.017), P < 0.0001]. No magnesium-related SNP or interaction between any SNP and magnesium reached significance after correction for multiple testing. However, rs2274924 in magnesium transporter-encoding TRPM6 showed a nominal association (uncorrected P = 0.03) with glucose, and rs11558471 in SLC30A8 and rs3740393 near CNNM2 showed a nominal interaction (uncorrected, both P = 0.02) with magnesium on glucose. Consistent with other studies, a higher magnesium intake was associated with lower fasting glucose and insulin. Nominal evidence of TRPM6 influence and magnesium interaction with select loci suggests that further investigation is warranted.
Keywords: Blood Glucose; Female; Genetic Loci; Humans; Insulin; Magnesium; Male; Polymorphism, Single Nucleotide; Trace Elements; TRPM Cation Channels

Identification of heart rate-associated loci and their effects on cardiac conduction and rhythm disorders. - den Hoed, Marcel; Eijgelsheim, Mark; Esko, Tõnu; Brundel, Bianca J J M; Peal, David S; Evans, David M; Nolte, Ilja M; Segrè, Ayellet V; Holm, Hilma; Handsaker, Robert E; Westra, Harm-Jan; Johnson, Toby; et al. (Nat Genet, 2013)
Elevated resting heart rate is associated with greater risk of cardiovascular disease and mortality. In a 2-stage meta-analysis of genome-wide association studies in up to 181,171 individuals, we identified 14 new loci associated with heart rate and confirmed associations with all 7 previously established loci. Experimental downregulation of gene expression in Drosophila melanogaster and Danio rerio identified 20 genes at 11 loci that are relevant for heart rate regulation and highlight a role for genes involved in signal transmission, embryonic cardiac development and the pathophysiology of dilated cardiomyopathy, congenital heart failure and/or sudden cardiac death. In addition, genetic susceptibility to increased heart rate is associated with altered cardiac conduction and reduced risk of sick sinus syndrome, and both heart rate-increasing and heart rate-decreasing variants associate with risk of atrial fibrillation. Our findings provide fresh insights into the mechanisms regulating heart rate and identify new therapeutic targets.
Keywords: Animals; Arrhythmias, Cardiac; Gene Frequency; Genetic Loci; Genome-Wide Association Study; Heart Conduction System; Heart Rate; Humans; Metabolic Networks and Pathways; Polymorphism, Single Nucleotide; Quantitative Trait Loci

Impact of inflammatory biomarkers on relation of high density lipoprotein-cholesterol with incident coronary heart disease: cardiovascular Health Study. - Tehrani, David M; Gardin, Julius M; Yanez, David; Hirsch, Calvin H; Lloyd-Jones, Donald M; Stein, Phyllis K; Wong, Nathan D (Atherosclerosis, 2013)
BACKGROUND: Inflammatory factors and low HDL-C relate to CHD risk, but whether inflammation attenuates any protective association of high HDL-C is unknown. OBJECTIVE: Investigate inflammatory markers' individual and collective impact on the association of HDL-C with incident coronary heart disease (CHD). METHODS: In 3888 older adults without known cardiovascular disease (CVD), we examined if the inflammatory markers C-reactive protein (CRP), interleukin-6 (IL-6), and lipoprotein-associated phospholipase A2 (Lp-PLA₂) modify the relation of HDL-C with CHD. HDL-C, CRP, IL-6, and Lp-PLA₂ values were grouped as using gender-specific tertiles. Also, an inflammation index of z-score sums for CRP, IL-6, and Lp-PLA₂ was categorized into tertiles. We calculated CHD incidence for each HDL-C/inflammation group and performed Cox regression, adjusted for standard CVD risk factors and triglycerides to examine the relationship of combined HDL-C-inflammation groups with incident events. RESULTS: CHD incidence (per 1000 person years) was higher for higher levels of CRP, IL-6, and the index, and lower for higher levels of HDL-C. Compared to high HDL-C/low-inflammation categories (referent), adjusted HRs for incident CHD were increased for those with high HDL-C and high CRP (HR = 1.50, p < 0.01) or highest IL-6 tertile (HR = 1.40, p < 0.05), but not with highest Lp-PLA₂ tertile. Higher CHD incidence was similarly seen for those with intermediate or low HDL-C accompanied by high CRP, high IL-6, or a high inflammatory index. CONCLUSION: The protective relation of high HDL-C for incident CHD appears to be attenuated by greater inflammation.
Keywords: 1-Alkyl-2-acetylglycerophosphocholine Esterase; African Americans; Aged; Biomarkers; C-Reactive Protein; Cardiovascular Diseases; Cholesterol, HDL; Coronary Disease; European Continental Ancestry Group; Female; Humans; Incidence; Inflammation; Interleukin-6; Male; Middle Aged; Proportional Hazards Models; Prospective Studies; Risk Factors

The influence of obesity-related single nucleotide polymorphisms on BMI across the life course: the PAGE study. - Graff, Mariaelisa; Gordon-Larsen, Penny; Lim, Unhee; Fowke, Jay H; Love, Shelly-Ann; Fesinmeyer, Megan; Wilkens, Lynne R; Vertilus, Shawyntee; Ritchie, Marilyn D; Prentice, Ross L; Pankow, Jim; Monroe, Kristine; et al. (Diabetes, 2013)
Evidence is limited as to whether heritable risk of obesity varies throughout adulthood. Among >34,000 European Americans, aged 18-100 years, from multiple U.S. studies in the Population Architecture using Genomics and Epidemiology (PAGE) Consortium, we examined evidence for heterogeneity in the associations of five established obesity risk variants (near FTO, GNPDA2, MTCH2, TMEM18, and NEGR1) with BMI across four distinct epochs of adulthood: 1) young adulthood (ages 18-25 years), adulthood (ages 26-49 years), middle-age adulthood (ages 50-69 years), and older adulthood (ages ≥70 years); or 2) by menopausal status in women and stratification by age 50 years in men. Summary-effect estimates from each meta-analysis were compared for heterogeneity across the life epochs. We found heterogeneity in the association of the FTO (rs8050136) variant with BMI across the four adulthood epochs (P = 0.0006), with larger effects in young adults relative to older adults (β [SE] = 1.17 [0.45] vs. 0.09 [0.09] kg/m², respectively, per A allele) and smaller intermediate effects. We found no evidence for heterogeneity in the association of GNPDA2, MTCH2, TMEM18, and NEGR1 with BMI across adulthood. Genetic predisposition to obesity may have greater effects on body weight in young compared with older adulthood for FTO, suggesting changes by age, generation, or secular trends. Future research should compare and contrast our findings with results using longitudinal data.
Keywords: Adolescent; Adult; Aged; Aged, 80 and over; Aging; Body Mass Index; Cohort Studies; Cross-Sectional Studies; European Continental Ancestry Group; Female; Genetic Association Studies; Health Surveys; Humans; Male; Middle Aged; Obesity; Polymorphism, Single Nucleotide; Proteins; United States; Young Adult

Insights into the genetic architecture of early stage age-related macular degeneration: a genome-wide association study meta-analysis. - Holliday, Elizabeth G; Smith, Albert V; Cornes, Belinda K; Buitendijk, Gabriëlle H S; Jensen, Richard A; Sim, Xueling; Aspelund, Thor; Aung, Tin; Baird, Paul N; Boerwinkle, Eric; Cheng, Ching Yu; van Duijn, Cornelia M; et al. (PLoS One, 2013)
Genetic factors explain a majority of risk variance for age-related macular degeneration (AMD). While genome-wide association studies (GWAS) for late AMD implicate genes in complement, inflammatory and lipid pathways, the genetic architecture of early AMD has been relatively under studied. We conducted a GWAS meta-analysis of early AMD, including 4,089 individuals with prevalent signs of early AMD (soft drusen and/or retinal pigment epithelial changes) and 20,453 individuals without these signs. For various published late AMD risk loci, we also compared effect sizes between early and late AMD using an additional 484 individuals with prevalent late AMD. GWAS meta-analysis confirmed previously reported association of variants at the complement factor H (CFH) (peak P = 1.5×10(-31)) and age-related maculopathy susceptibility 2 (ARMS2) (P = 4.3×10(-24)) loci, and suggested Apolipoprotein E (ApoE) polymorphisms (rs2075650; P = 1.1×10(-6)) associated with early AMD. Other possible loci that did not reach GWAS significance included variants in the zinc finger protein gene GLI3 (rs2049622; P = 8.9×10(-6)) and upstream of GLI2 (rs6721654; P = 6.5×10(-6)), encoding retinal Sonic hedgehog signalling regulators, and in the tyrosinase (TYR) gene (rs621313; P = 3.5×10(-6)), involved in melanin biosynthesis. For a range of published, late AMD risk loci, estimated effect sizes were significantly lower for early than late AMD. This study confirms the involvement of multiple established AMD risk variants in early AMD, but suggests weaker genetic effects on the risk of early AMD relative to late AMD. Several biological processes were suggested to be potentially specific for early AMD, including pathways regulating RPE cell melanin content and signalling pathways potentially involved in retinal regeneration, generating hypotheses for further investigation.
Keywords: Apolipoproteins E; Complement Factor H; Genetic Predisposition to Disease; Genome-Wide Association Study; Genotype; Humans; Kruppel-Like Transcription Factors; Macular Degeneration; Nerve Tissue Proteins; Polymorphism, Single Nucleotide; Proteins; Risk Factors; Zinc Finger Protein Gli3

Investigation of gene-by-sex interactions for lipid traits in diverse populations from the population architecture using genomics and epidemiology study. - Taylor, Kira C; Carty, Cara L; Dumitrescu, Logan; Bůzková, Petra; Cole, Shelley A; Hindorff, Lucia; Schumacher, Fred R; Wilkens, Lynne R; Shohet, Ralph V; Quibrera, P Miguel; Johnson, Karen C; Henderson, Brian E; et al. (BMC Genet, 2013)
BACKGROUND: High-density lipoprotein cholesterol (HDL-C), low-density lipoprotein cholesterol (LDL-C), and triglyceride (TG) levels are influenced by both genes and the environment. Genome-wide association studies (GWAS) have identified ~100 common genetic variants associated with HDL-C, LDL-C, and/or TG levels, mostly in populations of European descent, but little is known about the modifiers of these associations. Here, we investigated whether GWAS-identified SNPs for lipid traits exhibited heterogeneity by sex in the Population Architecture using Genomics and Epidemiology (PAGE) study. RESULTS: A sex-stratified meta-analysis was performed for 49 GWAS-identified SNPs for fasting HDL-C, LDL-C, and ln(TG) levels among adults self-identified as European American (25,013). Heterogeneity by sex was established when phet < 0.001. There was evidence for heterogeneity by sex for two SNPs for ln(TG) in the APOA1/C3/A4/A5/BUD13 gene cluster: rs28927680 (p(het) = 7.4 x 10(-7)) and rs3135506 (p(het) = 4.3 x 10(-4)one SNP in PLTP for HDL levels (rs7679; p(het) = 9.9 x 10(-4)), and one in HMGCR for LDL levels (rs12654264; p(het) = 3.1 x 10(-5)). We replicated heterogeneity by sex in five of seventeen loci previously reported by genome-wide studies (binomial p = 0.0009). We also present results for other racial/ethnic groups in the supplementary materials, to provide a resource for future meta-analyses. CONCLUSIONS: We provide further evidence for sex-specific effects of SNPs in the APOA1/C3/A4/A5/BUD13 gene cluster, PLTP, and HMGCR on fasting triglyceride levels in European Americans from the PAGE study. Our findings emphasize the need for considering context-specific effects when interpreting genetic associations emerging from GWAS, and also highlight the difficulties in replicating interaction effects across studies and across racial/ethnic groups.
Keywords: Female; Genetic Heterogeneity; Genome, Human; Genome-Wide Association Study; Humans; Lipids; Male; Polymorphism, Single Nucleotide; Population Groups

Ischemic stroke is associated with the ABO locus: the EuroCLOT study. - Williams, Frances M K; Carter, Angela M; Hysi, Pirro G; Surdulescu, Gabriela; Hodgkiss, Dylan; Soranzo, Nicole; Traylor, Matthew; Bevan, Steve; Dichgans, Martin; Rothwell, Peter M W; Sudlow, Cathie; Farrall, Martin; et al. (Ann Neurol, 2013)
OBJECTIVE: End-stage coagulation and the structure/function of fibrin are implicated in the pathogenesis of ischemic stroke. We explored whether genetic variants associated with end-stage coagulation in healthy volunteers account for the genetic predisposition to ischemic stroke and examined their influence on stroke subtype. METHODS: Common genetic variants identified through genome-wide association studies of coagulation factors and fibrin structure/function in healthy twins (n = 2,100, Stage 1) were examined in ischemic stroke (n = 4,200 cases) using 2 independent samples of European ancestry (Stage 2). A third clinical collection having stroke subtyping (total 8,900 cases, 55,000 controls) was used for replication (Stage 3). RESULTS: Stage 1 identified 524 single nucleotide polymorphisms (SNPs) from 23 linkage disequilibrium blocks having significant association (p < 5 × 10(-8)) with 1 or more coagulation/fibrin phenotypes. The most striking associations included SNP rs5985 with factor XIII activity (p = 2.6 × 10(-186)), rs10665 with FVII (p = 2.4 × 10(-47)), and rs505922 in the ABO gene with both von Willebrand factor (p = 4.7 × 10(-57)) and factor VIII (p = 1.2 × 10(-36)). In Stage 2, the 23 independent SNPs were examined in stroke cases/noncases using MOnica Risk, Genetics, Archiving and Monograph (MORGAM) and Wellcome Trust Case Control Consortium 2 collections. SNP rs505922 was nominally associated with ischemic stroke (odds ratio = 0.94, 95% confidence interval = 0.88-0.99, p = 0.023). Independent replication in Meta-Stroke confirmed the rs505922 association with stroke, beta (standard error, SE) = 0.066 (0.02), p = 0.001, a finding specific to large-vessel and cardioembolic stroke (p = 0.001 and p = < 0.001, respectively) but not seen with small-vessel stroke (p = 0.811). INTERPRETATION: ABO gene variants are associated with large-vessel and cardioembolic stroke but not small-vessel disease. This work sheds light on the different pathogenic mechanisms underpinning stroke subtype.
Keywords: ABO Blood-Group System; Adolescent; Adult; Aged; Aged, 80 and over; Blood Coagulation; Brain Ischemia; Cohort Studies; Europe; Female; Genetic Loci; Genetic Predisposition to Disease; Genetic Variation; Genome-Wide Association Study; Humans; Male; Middle Aged; Polymorphism, Single Nucleotide; Stroke; Young Adult

Lack of associations of ten candidate coronary heart disease risk genetic variants and subclinical atherosclerosis in four US populations: the Population Architecture using Genomics and Epidemiology (PAGE) study. - Zhang, Lili; Bůzková, Petra; Wassel, Christina L; Roman, Mary J; North, Kari E; Crawford, Dana C; Boston, Jonathan; Brown-Gentry, Kristin D; Cole, Shelley A; Deelman, Ewa; Goodloe, Robert; Wilson, Sarah; et al. (Atherosclerosis, 2013)
BACKGROUND: A number of genetic variants have been discovered by recent genome-wide association studies for their associations with clinical coronary heart disease (CHD). However, it is unclear whether these variants are also associated with the development of CHD as measured by subclinical atherosclerosis phenotypes, ankle brachial index (ABI), carotid artery intima-media thickness (cIMT) and carotid plaque. METHODS: Ten CHD risk single nucleotide polymorphisms (SNPs) were genotyped in individuals of European American (EA), African American (AA), American Indian (AI), and Mexican American (MA) ancestry in the Population Architecture using Genomics and Epidemiology (PAGE) study. In each individual study, we performed linear or logistic regression to examine population-specific associations between SNPs and ABI, common and internal cIMT, and plaque. The results from individual studies were meta-analyzed using a fixed effect inverse variance weighted model. RESULTS: None of the ten SNPs was significantly associated with ABI and common or internal cIMT, after Bonferroni correction. In the sample of 13,337 EA, 3809 AA, and 5353 AI individuals with carotid plaque measurement, the GCKR SNP rs780094 was significantly associated with the presence of plaque in AI only (OR = 1.32, 95% confidence interval: 1.17, 1.49, P = 1.08 × 10(-5)), but not in the other populations (P = 0.90 in EA and P = 0.99 in AA). A 9p21 region SNP, rs1333049, was nominally associated with plaque in EA (OR = 1.07, P = 0.02) and in AI (OR = 1.10, P = 0.05). CONCLUSIONS: We identified a significant association between rs780094 and plaque in AI populations, which needs to be replicated in future studies. There was little evidence that the index CHD risk variants identified through genome-wide association studies in EA influence the development of CHD through subclinical atherosclerosis as assessed by cIMT and ABI across ancestries.
Keywords: African Americans; Aged; Ankle Brachial Index; Asymptomatic Diseases; Carotid Artery Diseases; Carotid Intima-Media Thickness; Coronary Disease; European Continental Ancestry Group; Female; Gene Frequency; Genetic Association Studies; Genetic Predisposition to Disease; Humans; Indians, North American; Linear Models; Logistic Models; Male; Mexican Americans; Middle Aged; Odds Ratio; Phenotype; Polymorphism, Single Nucleotide; Predictive Value of Tests; Risk Assessment; Risk Factors; United States

Lipoprotein receptor-related protein 1 variants and dietary fatty acids: meta-analysis of European origin and African American studies. - Smith, C E; Ngwa, J; Tanaka, T; Qi, Q; Wojczynski, M K; Lemaitre, R N; Anderson, J S; Manichaikul, A; Mikkilä, V; van Rooij, F J A; Ye, Z; Bandinelli, S; et al. (Int J Obes (Lond), 2013)
OBJECTIVE: Low-density lipoprotein-related receptor protein 1 (LRP1) is a multi-functional endocytic receptor and signaling molecule that is expressed in adipose and the hypothalamus. Evidence for a role of LRP1 in adiposity is accumulating from animal and in vitro models, but data from human studies are limited. The study objectives were to evaluate (i) relationships between LRP1 genotype and anthropometric traits, and (ii) whether these relationships were modified by dietary fatty acids. DESIGN AND METHODS: We conducted race/ethnic-specific meta-analyses using data from 14 studies of US and European whites and 4 of African Americans to evaluate associations of dietary fatty acids and LRP1 genotypes with body mass index (BMI), waist circumference and hip circumference, as well as interactions between dietary fatty acids and LRP1 genotypes. Seven single-nucleotide polymorphisms (SNPs) of LRP1 were evaluated in whites (N up to 42 000) and twelve SNPs in African Americans (N up to 5800). RESULTS: After adjustment for age, sex and population substructure if relevant, for each one unit greater intake of percentage of energy from saturated fat (SFA), BMI was 0.104 kg m(-2) greater, waist was 0.305 cm larger and hip was 0.168 cm larger (all P<0.0001). Other fatty acids were not associated with outcomes. The association of SFA with outcomes varied by genotype at rs2306692 (genotyped in four studies of whites), where the magnitude of the association of SFA intake with each outcome was greater per additional copy of the T allele: 0.107 kg m(-2) greater for BMI (interaction P=0.0001), 0.267 cm for waist (interaction P=0.001) and 0.21 cm for hip (interaction P=0.001). No other significant interactions were observed. CONCLUSION: Dietary SFA and LRP1 genotype may interactively influence anthropometric traits. Further exploration of this, and other diet x genotype interactions, may improve understanding of interindividual variability in the relationships of dietary factors with anthropometric traits.
Keywords: Adipose Tissue; Adult; African Continental Ancestry Group; Aged; Aged, 80 and over; Body Mass Index; Europe; European Continental Ancestry Group; Fatty Acids; Female; Gene Frequency; Gene-Environment Interaction; Genetic Predisposition to Disease; Genotype; Humans; Low Density Lipoprotein Receptor-Related Protein-1; Male; Middle Aged; Obesity; Phenotype; Polymorphism, Single Nucleotide; Prevalence; United States

A meta-analysis identifies new loci associated with body mass index in individuals of African ancestry. - Monda, Keri L; Chen, Gary K; Taylor, Kira C; Palmer, Cameron; Edwards, Todd L; Lange, Leslie A; Ng, Maggie C Y; Adeyemo, Adebowale A; Allison, Matthew A; Bielak, Lawrence F; Chen, Guanjie; Graff, Mariaelisa; et al. (Nat Genet, 2013)
Genome-wide association studies (GWAS) have identified 36 loci associated with body mass index (BMI), predominantly in populations of European ancestry. We conducted a meta-analysis to examine the association of >3.2 million SNPs with BMI in 39,144 men and women of African ancestry and followed up the most significant associations in an additional 32,268 individuals of African ancestry. We identified one new locus at 5q33 (GALNT10, rs7708584, P = 3.4 × 10(-11)) and another at 7p15 when we included data from the GIANT consortium (MIR148A-NFE2L3, rs10261878, P = 1.2 × 10(-10)). We also found suggestive evidence of an association at a third locus at 6q16 in the African-ancestry sample (KLHL32, rs974417, P = 6.9 × 10(-8)). Thirty-two of the 36 previously established BMI variants showed directionally consistent effect estimates in our GWAS (binomial P = 9.7 × 10(-7)), five of which reached genome-wide significance. These findings provide strong support for shared BMI loci across populations, as well as for the utility of studying ancestrally diverse populations.
Keywords: African Americans; Body Mass Index; Case-Control Studies; Gene Frequency; Genetic Loci; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Linkage Disequilibrium; Obesity; Polymorphism, Single Nucleotide

Meta-analysis of 74,046 individuals identifies 11 new susceptibility loci for Alzheimer's disease. - Lambert, J C; Ibrahim-Verbaas, C A; Harold, D; Naj, A C; Sims, R; Bellenguez, C; DeStafano, A L; Bis, J C; Beecham, G W; Grenier-Boley, B; Russo, G; Thorton-Wells, T A; et al. (Nat Genet, 2013)
Eleven susceptibility loci for late-onset Alzheimer's disease (LOAD) were identified by previous studies; however, a large portion of the genetic risk for this disease remains unexplained. We conducted a large, two-stage meta-analysis of genome-wide association studies (GWAS) in individuals of European ancestry. In stage 1, we used genotyped and imputed data (7,055,881 SNPs) to perform meta-analysis on 4 previously published GWAS data sets consisting of 17,008 Alzheimer's disease cases and 37,154 controls. In stage 2, 11,632 SNPs were genotyped and tested for association in an independent set of 8,572 Alzheimer's disease cases and 11,312 controls. In addition to the APOE locus (encoding apolipoprotein E), 19 loci reached genome-wide significance (P < 5 × 10(-8)) in the combined stage 1 and stage 2 analysis, of which 11 are newly associated with Alzheimer's disease.
Keywords: Age of Onset; Aged; Aged, 80 and over; Alzheimer Disease; Case-Control Studies; Cohort Studies; Female; Genetic Loci; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Male; Middle Aged; Polymorphism, Single Nucleotide

Meta-analysis of genome-wide association studies identifies six new Loci for serum calcium concentrations. - O'Seaghdha, Conall M; Wu, Hongsheng; Yang, Qiong; Kapur, Karen; Guessous, Idris; Zuber, Annie Mercier; Köttgen, Anna; Stoudmann, Candice; Teumer, Alexander; Kutalik, Zoltán; Mangino, Massimo; Dehghan, Abbas; et al. (PLoS Genet, 2013)
Calcium is vital to the normal functioning of multiple organ systems and its serum concentration is tightly regulated. Apart from CASR, the genes associated with serum calcium are largely unknown. We conducted a genome-wide association meta-analysis of 39,400 individuals from 17 population-based cohorts and investigated the 14 most strongly associated loci in ≤ 21,679 additional individuals. Seven loci (six new regions) in association with serum calcium were identified and replicated. Rs1570669 near CYP24A1 (P = 9.1E-12), rs10491003 upstream of GATA3 (P = 4.8E-09) and rs7481584 in CARS (P = 1.2E-10) implicate regions involved in Mendelian calcemic disorders: Rs1550532 in DGKD (P = 8.2E-11), also associated with bone density, and rs7336933 near DGKH/KIAA0564 (P = 9.1E-10) are near genes that encode distinct isoforms of diacylglycerol kinase. Rs780094 is in GCKR. We characterized the expression of these genes in gut, kidney, and bone, and demonstrate modulation of gene expression in bone in response to dietary calcium in mice. Our results shed new light on the genetics of calcium homeostasis.
Keywords: Animals; Bone and Bones; Bone Density; Calcium; European Continental Ancestry Group; Gene Expression Regulation; Genome-Wide Association Study; Homeostasis; Humans; Kidney; Mice; Polymorphism, Single Nucleotide

A meta-analysis of thyroid-related traits reveals novel loci and gender-specific differences in the regulation of thyroid function. - Porcu, Eleonora; Medici, Marco; Pistis, Giorgio; Volpato, Claudia B; Wilson, Scott G; Cappola, Anne R; Bos, Steffan D; Deelen, Joris; den Heijer, Martin; Freathy, Rachel M; Lahti, Jari; Liu, Chunyu; et al. (PLoS Genet, 2013)
Thyroid hormone is essential for normal metabolism and development, and overt abnormalities in thyroid function lead to common endocrine disorders affecting approximately 10% of individuals over their life span. In addition, even mild alterations in thyroid function are associated with weight changes, atrial fibrillation, osteoporosis, and psychiatric disorders. To identify novel variants underlying thyroid function, we performed a large meta-analysis of genome-wide association studies for serum levels of the highly heritable thyroid function markers TSH and FT4, in up to 26,420 and 17,520 euthyroid subjects, respectively. Here we report 26 independent associations, including several novel loci for TSH (PDE10A, VEGFA, IGFBP5, NFIA, SOX9, PRDM11, FGF7, INSR, ABO, MIR1179, NRG1, MBIP, ITPK1, SASH1, GLIS3) and FT4 (LHX3, FOXE1, AADAT, NETO1/FBXO15, LPCAT2/CAPNS2). Notably, only limited overlap was detected between TSH and FT4 associated signals, in spite of the feedback regulation of their circulating levels by the hypothalamic-pituitary-thyroid axis. Five of the reported loci (PDE8B, PDE10A, MAF/LOC440389, NETO1/FBXO15, and LPCAT2/CAPNS2) show strong gender-specific differences, which offer clues for the known sexual dimorphism in thyroid function and related pathologies. Importantly, the TSH-associated loci contribute not only to variation within the normal range, but also to TSH values outside the reference range, suggesting that they may be involved in thyroid dysfunction. Overall, our findings explain, respectively, 5.64% and 2.30% of total TSH and FT4 trait variance, and they improve the current knowledge of the regulation of hypothalamic-pituitary-thyroid axis function and the consequences of genetic variation for hypo- or hyperthyroidism.
Keywords: Female; Genome-Wide Association Study; Humans; Hyperthyroidism; Hypothyroidism; Male; Phenotype; Polymorphism, Genetic; Polymorphism, Single Nucleotide; Sex Characteristics; Signal Transduction; Thyroid Gland; Thyrotropin; Thyroxine

Multiethnic meta-analysis of genome-wide association studies in >100 000 subjects identifies 23 fibrinogen-associated Loci but no strong evidence of a causal association between circulating fibrinogen and cardiovascular disease. - Sabater-Lleal, Maria; Huang, Jie; Chasman, Daniel; Naitza, Silvia; Dehghan, Abbas; Johnson, Andrew D; Teumer, Alexander; Reiner, Alex P; Folkersen, Lasse; Basu, Saonli; Rudnicka, Alicja R; Trompet, Stella; et al. (Circulation, 2013)
BACKGROUND: Estimates of the heritability of plasma fibrinogen concentration, an established predictor of cardiovascular disease, range from 34% to 50%. Genetic variants so far identified by genome-wide association studies explain only a small proportion (<2%) of its variation. METHODS AND RESULTS: We conducted a meta-analysis of 28 genome-wide association studies including >90 000 subjects of European ancestry, the first genome-wide association meta-analysis of fibrinogen levels in 7 studies in blacks totaling 8289 samples, and a genome-wide association study in Hispanics totaling 1366 samples. Evaluation for association of single-nucleotide polymorphisms with clinical outcomes included a total of 40 695 cases and 85 582 controls for coronary artery disease, 4752 cases and 24 030 controls for stroke, and 3208 cases and 46 167 controls for venous thromboembolism. Overall, we identified 24 genome-wide significant (P<5×10(-8)) independent signals in 23 loci, including 15 novel associations, together accounting for 3.7% of plasma fibrinogen variation. Gene-set enrichment analysis highlighted key roles in fibrinogen regulation for the 3 structural fibrinogen genes and pathways related to inflammation, adipocytokines, and thyrotrophin-releasing hormone signaling. Whereas lead single-nucleotide polymorphisms in a few loci were significantly associated with coronary artery disease, the combined effect of all 24 fibrinogen-associated lead single-nucleotide polymorphisms was not significant for coronary artery disease, stroke, or venous thromboembolism. CONCLUSIONS: We identify 23 robustly associated fibrinogen loci, 15 of which are new. Clinical outcome analysis of these loci does not support a causal relationship between circulating levels of fibrinogen and coronary artery disease, stroke, or venous thromboembolism.
Keywords: Adolescent; Adult; African Continental Ancestry Group; Aged; Aged, 80 and over; Cardiovascular Diseases; Coronary Artery Disease; European Continental Ancestry Group; Female; Fibrinogen; Genetic Loci; Genetic Predisposition to Disease; Genome-Wide Association Study; Hispanic Americans; Humans; Male; Middle Aged; Myocardial Infarction; Polymorphism, Single Nucleotide; Risk Factors; Stroke; Venous Thromboembolism; Young Adult

No evidence of interaction between known lipid-associated genetic variants and smoking in the multi-ethnic PAGE population. - Dumitrescu, Logan; Carty, Cara L; Franceschini, Nora; Hindorff, Lucia A; Cole, Shelley A; Bůzková, Petra; Schumacher, Fredrick R; Eaton, Charles B; Goodloe, Robert J; Duggan, David J; Haessler, Jeff; Cochran, Barbara; et al. (Hum Genet, 2013)
Genome-wide association studies (GWAS) have identified many variants that influence high-density lipoprotein cholesterol, low-density lipoprotein cholesterol, and/or triglycerides. However, environmental modifiers, such as smoking, of these known genotype-phenotype associations are just recently emerging in the literature. We have tested for interactions between smoking and 49 GWAS-identified variants in over 41,000 racially/ethnically diverse samples with lipid levels from the Population Architecture Using Genomics and Epidemiology (PAGE) study. Despite their biological plausibility, we were unable to detect significant SNP × smoking interactions.
Keywords: Cholesterol, HDL; Cholesterol, LDL; Cohort Studies; Ethnic Groups; Female; Gene Frequency; Gene-Environment Interaction; Genetics, Population; Genome-Wide Association Study; Humans; Lipid Metabolism; Male; Polymorphism, Single Nucleotide; Prevalence; Smoking; Triglycerides; Young Adult

Obesity is associated with a lower resting oxygen saturation in the ambulatory elderly: results from the cardiovascular health study. - Kapur, Vishesh K; Wilsdon, Anthony G; Au, David; Avdalovic, Mark; Enright, Paul; Fan, Vincent S; Hansel, Nadia N; Heckbert, Susan R; Jiang, Rui; Krishnan, Jerry A; Mukamal, Kenneth; Yende, Sachin; et al. (Respir Care, 2013)
BACKGROUND: The contribution of obesity to hypoxemia has not been reported in a community-based study. Our hypothesis was that increasing obesity would be independently associated with lower SpO2 in an ambulatory elderly population. METHODS: The Cardiovascular Health Study ascertained resting SpO2 in 2,252 subjects over age 64. We used multiple linear regression to estimate the association of body mass index (BMI) with SpO2 and to adjust for potentially confounding factors. Covariates including age, sex, race, smoking, airway obstruction (based on spirometry), self reported diagnosis of emphysema, asthma, heart failure, and left ventricular function (by echocardiography) were evaluated. RESULTS: Among 2,252 subjects the mean and median SpO2 were 97.6% and 98.0% respectively; 5% of subjects had SpO2 values below 95%. BMI was negatively correlated with SpO2 (Spearman R = -0.27, P < .001). The mean difference in SpO2 between the lowest and highest BMI categories (< 25 kg/m(2) and ≥ 35 kg/m(2)) was 1.33% (95% CI 0.89-1.78%). In multivariable linear regression analysis, SpO2 was significantly inversely associated with BMI (1.4% per 10 units of BMI, 95% CI 1.2-1.6, for whites/others, and 0.87% per 10 units of BMI, 95% CI 0.47-1.27, for African Americans). CONCLUSIONS: We found a narrow distribution of SpO2 values in a community-based sample of ambulatory elderly. Obesity was a strong independent contributor to a low SpO2, with effects comparable to or greater than other factors clinically associated with lower SpO2.
Keywords: African Americans; Age Factors; Aged; Aged, 80 and over; Body Mass Index; European Continental Ancestry Group; Female; Humans; Male; Obesity; Oximetry; Oxygen; Smoking; Waist Circumference

Plasma phospholipid long-chain ω-3 fatty acids and total and cause-specific mortality in older adults: a cohort study. - Mozaffarian, Dariush; Lemaitre, Rozenn N; King, Irena B; Song, Xiaoling; Huang, Hongyan; Sacks, Frank M; Rimm, Eric B; Wang, Molin; Siscovick, David S (Ann Intern Med, 2013)
BACKGROUND: Long-chain ω-3 polyunsaturated fatty acids (ω3-PUFAs), including eicosapentaenoic acid (EPA) (20:5ω-3), docosapentaenoic acid (DPA) (22:5ω-3), and docosahexaenoic acid (DHA) (22:6ω-3), have been shown to reduce cardiovascular risk, but effects on cause-specific and total mortality and potential dose-responses remain controversial. Most observational studies have assessed self-reported dietary intake and most randomized trials have tested effects of adding supplements to dietary intake and evaluated secondary prevention, thus limiting inference for dietary ω3-PUFAs or primary prevention. OBJECTIVE: To investigate associations of plasma phospholipid EPA, DPA, DHA, and total ω3-PUFA levels with total and cause-specific mortality among healthy older adults not receiving supplements. DESIGN: Prospective cohort study. SETTING: 4 U.S. communities. PARTICIPANTS: 2692 U.S. adults aged 74 years (±5 years) without prevalent coronary heart disease (CHD), stroke, or heart failure at baseline. MEASUREMENTS: Phospholipid fatty acid levels and cardiovascular risk factors were measured in 1992. Relationships with total and cause-specific mortality and incident fatal or nonfatal CHD and stroke through 2008 were assessed. RESULTS: During 30 829 person-years, 1625 deaths (including 570 cardiovascular deaths), 359 fatal and 371 nonfatal CHD events, and 130 fatal and 276 nonfatal strokes occurred. After adjustment, higher plasma levels of ω3-PUFA biomarkers were associated with lower total mortality, with extreme-quintile hazard ratios of 0.83 for EPA (95% CI, 0.71 to 0.98; P for trend = 0.005), 0.77 for DPA (CI, 0.66 to 0.90; P for trend = 0.008), 0.80 for DHA (CI, 0.67 to 0.94; P for trend = 0.006), and 0.73 for total ω3-PUFAs (CI, 0.61 to 0.86; P for trend < 0.001). Lower risk was largely attributable to fewer cardiovascular than noncardiovascular deaths. Individuals in the highest quintile of phospholipid ω3-PUFA level lived an average of 2.22 more years (CI, 0.75 to 3.13 years) after age 65 years than did those in the lowest quintile. LIMITATION: Temporal changes in fatty acid levels and misclassification of causes of death may have resulted in underestimated associations, and unmeasured or imperfectly measured covariates may have caused residual confounding. CONCLUSION: Higher circulating individual and total ω3-PUFA levels are associated with lower total mortality, especially CHD death, in older adults. PRIMARY FUNDING SOURCE: National Institutes of Health.
Keywords: Aged; Biomarkers; Cause of Death; Coronary Disease; Diet Records; Docosahexaenoic Acids; Eicosapentaenoic Acid; Fatty Acids, Omega-3; Fatty Acids, Unsaturated; Feeding Behavior; Female; Humans; Male; Prospective Studies; Risk Assessment; Stroke

Post-genome-wide association study challenges for lipid traits: describing age as a modifier of gene-lipid associations in the Population Architecture using Genomics and Epidemiology (PAGE) study. - Dumitrescu, Logan; Carty, Cara L; Franceschini, Nora; Hindorff, Lucia A; Cole, Shelley A; Bůzková, Petra; Schumacher, Fredrick R; Eaton, Charles B; Goodloe, Robert J; Duggan, David J; Haessler, Jeff; Cochran, Barbara; et al. (Ann Hum Genet, 2013)
Numerous common genetic variants that influence plasma high-density lipoprotein cholesterol, low-density lipoprotein cholesterol (LDL-C), and triglyceride distributions have been identified via genome-wide association studies (GWAS). However, whether or not these associations are age-dependent has largely been overlooked. We conducted an association study and meta-analysis in more than 22,000 European Americans between 49 previously identified GWAS variants and the three lipid traits, stratified by age (males: <50 or ≥50 years of age; females: pre- or postmenopausal). For each variant, a test of heterogeneity was performed between the two age strata and significant Phet values were used as evidence of age-specific genetic effects. We identified seven associations in females and eight in males that displayed suggestive heterogeneity by age (Phet < 0.05). The association between rs174547 (FADS1) and LDL-C in males displayed the most evidence for heterogeneity between age groups (Phet = 1.74E-03, I(2) = 89.8), with a significant association in older males (P = 1.39E-06) but not younger males (P = 0.99). However, none of the suggestive modifying effects survived adjustment for multiple testing, highlighting the challenges of identifying modifiers of modest SNP-trait associations despite large sample sizes.
Keywords: Adult; Aged; European Continental Ancestry Group; Female; Genetic Association Studies; Genome-Wide Association Study; Humans; Lipids; Male; Middle Aged; Polymorphism, Single Nucleotide; Quantitative Trait Loci; Quantitative Trait, Heritable; Risk Factors

Replication of genetic loci for ages at menarche and menopause in the multi-ethnic Population Architecture using Genomics and Epidemiology (PAGE) study. - Carty, C L; Spencer, K L; Setiawan, V W; Fernandez-Rhodes, L; Malinowski, J; Buyske, S; Young, A; Jorgensen, N W; Cheng, I; Carlson, C S; Brown-Gentry, K; Goodloe, R; et al. (Hum Reprod, 2013)
STUDY QUESTION: Do genetic associations identified in genome-wide association studies (GWAS) of age at menarche (AM) and age at natural menopause (ANM) replicate in women of diverse race/ancestry from the Population Architecture using Genomics and Epidemiology (PAGE) Study? SUMMARY ANSWER: We replicated GWAS reproductive trait single nucleotide polymorphisms (SNPs) in our European descent population and found that many SNPs were also associated with AM and ANM in populations of diverse ancestry. WHAT IS KNOWN ALREADY: Menarche and menopause mark the reproductive lifespan in women and are important risk factors for chronic diseases including obesity, cardiovascular disease and cancer. Both events are believed to be influenced by environmental and genetic factors, and vary in populations differing by genetic ancestry and geography. Most genetic variants associated with these traits have been identified in GWAS of European-descent populations. STUDY DESIGN, SIZE, DURATION: A total of 42 251 women of diverse ancestry from PAGE were included in cross-sectional analyses of AM and ANM. MATERIALS, SETTING, METHODS: SNPs previously associated with ANM (n = 5 SNPs) and AM (n = 3 SNPs) in GWAS were genotyped in American Indians, African Americans, Asians, European Americans, Hispanics and Native Hawaiians. To test SNP associations with ANM or AM, we used linear regression models stratified by race/ethnicity and PAGE sub-study. Results were then combined in race-specific fixed effect meta-analyses for each outcome. For replication and generalization analyses, significance was defined at P < 0.01 for ANM analyses and P < 0.017 for AM analyses. MAIN RESULTS AND THE ROLE OF CHANCE: We replicated findings for AM SNPs in the LIN28B locus and an intergenic region on 9q31 in European Americans. The LIN28B SNPs (rs314277 and rs314280) were also significantly associated with AM in Asians, but not in other race/ethnicity groups. Linkage disequilibrium (LD) patterns at this locus varied widely among the ancestral groups. With the exception of an intergenic SNP at 13q34, all ANM SNPs replicated in European Americans. Three were significantly associated with ANM in other race/ethnicity populations: rs2153157 (6p24.2/SYCP2L), rs365132 (5q35/UIMC1) and rs16991615 (20p12.3/MCM8). While rs1172822 (19q13/BRSK1) was not significant in the populations of non-European descent, effect sizes showed similar trends. LIMITATIONS, REASONS FOR CAUTION: Lack of association for the GWAS SNPs in the non-European American groups may be due to differences in locus LD patterns between these groups and the European-descent populations included in the GWAS discovery studies; and in some cases, lower power may also contribute to non-significant findings. WIDER IMPLICATIONS OF THE FINDINGS: The discovery of genetic variants associated with the reproductive traits provides an important opportunity to elucidate the biological mechanisms involved with normal variation and disorders of menarche and menopause. In this study we replicated most, but not all reported SNPs in European descent populations and examined the epidemiologic architecture of these early reported variants, describing their generalizability and effect size across differing ancestral populations. Such data will be increasingly important for prioritizing GWAS SNPs for follow-up in fine-mapping and resequencing studies, as well as in translational research.
Keywords: Age Factors; Cross-Sectional Studies; Female; Genome-Wide Association Study; Genotype; Humans; Menarche; Menopause; Polymorphism, Single Nucleotide

Risk factors for hospital admission among older persons with newly diagnosed heart failure: findings from the Cardiovascular Health Study. - Chaudhry, Sarwat I; McAvay, Gail; Chen, Shu; Whitson, Heather; Newman, Anne B; Krumholz, Harlan M; Gill, Thomas M (J Am Coll Cardiol, 2013)
OBJECTIVES: This study sought to identify risk factors for the occurrence of all-cause hospital admissions among older persons after heart failure diagnosis, and to determine whether geriatric conditions would emerge as independent risk factors for admission when evaluated in the context of other relevant clinical data. BACKGROUND: Efforts to reduce costs in heart failure have focused on hospital utilization, yet few studies have examined how geriatric conditions affect the long-term risk for hospital admission after heart failure diagnosis. With the aging of the population with heart failure, geriatric conditions such as slow gait and muscle weakness are becoming increasingly common. METHODS: The study population included participants with a new diagnosis of heart failure in the Cardiovascular Health Study, a longitudinal study of community-living older persons. Data were collected through annual examinations and medical-record reviews. Geriatric conditions assessed were slow gait, muscle weakness (defined as weak grip), cognitive impairment, and depressive symptoms. Anderson-Gill regression modeling was used to determine the predictors of hospital admission after heart failure diagnosis. RESULTS: Of the 758 participants with a new diagnosis of heart failure, the mean rate of hospital admission was 7.9 per 10 person-years (95% CI: 7.4 to 8.4). Independent risk factors for hospital admission included diabetes mellitus (HR: 1.36; 95% CI: 1.13 to 1.64), New York Heart Association functional class III or IV (HR: 1.32; 95% CI: 1.11 to 1.57), chronic kidney disease (HR: 1.32; 95% CI: 1.14 to 1.53), slow gait (HR: 1.28; 95% CI: 1.06 to 1.55), depressed ejection fraction (HR: 1.25; 95% CI: 1.04 to 1.51), depression (HR: 1.23; 95% CI: 1.05 to 1.45), and muscle weakness (HR: 1.19; 95% CI: 1.00 to 1.42). CONCLUSIONS: Geriatric conditions are important, and potentially modifiable, risk factors for hospital admission in heart failure that should be routinely assessed at the time of heart failure diagnosis.
Keywords: Age Factors; Aged; Aged, 80 and over; Comorbidity; Effect Modifier, Epidemiologic; Female; Geriatric Assessment; Health Surveys; Heart Failure; Hospitalization; Humans; Longitudinal Studies; Male; Mental Competency; Risk Assessment; Risk Factors; Severity of Illness Index; Stroke Volume; Time-to-Treatment; United States

Sex-stratified genome-wide association studies including 270,000 individuals show sexual dimorphism in genetic loci for anthropometric traits. - Randall, Joshua C; Winkler, Thomas W; Kutalik, Zoltán; Berndt, Sonja I; Jackson, Anne U; Monda, Keri L; Kilpeläinen, Tuomas O; Esko, Tõnu; Mägi, Reedik; Li, Shengxu; Workalemahu, Tsegaselassie; Feitosa, Mary F; et al. (PLoS Genet, 2013)
Given the anthropometric differences between men and women and previous evidence of sex-difference in genetic effects, we conducted a genome-wide search for sexually dimorphic associations with height, weight, body mass index, waist circumference, hip circumference, and waist-to-hip-ratio (133,723 individuals) and took forward 348 SNPs into follow-up (additional 137,052 individuals) in a total of 94 studies. Seven loci displayed significant sex-difference (FDR<5%), including four previously established (near GRB14/COBLL1, LYPLAL1/SLC30A10, VEGFA, ADAMTS9) and three novel anthropometric trait loci (near MAP3K1, HSD17B4, PPARG), all of which were genome-wide significant in women (P<5×10(-8)), but not in men. Sex-differences were apparent only for waist phenotypes, not for height, weight, BMI, or hip circumference. Moreover, we found no evidence for genetic effects with opposite directions in men versus women. The PPARG locus is of specific interest due to its role in diabetes genetics and therapy. Our results demonstrate the value of sex-specific GWAS to unravel the sexually dimorphic genetic underpinning of complex traits.
Keywords: Anthropometry; Body Height; Body Mass Index; Body Weight; Body Weights and Measures; Female; Genetic Loci; Genome, Human; Genome-Wide Association Study; Humans; Male; Polymorphism, Single Nucleotide; Sex Characteristics; Waist Circumference; Waist-Hip Ratio

Simple risk model predicts incidence of atrial fibrillation in a racially and geographically diverse population: the CHARGE-AF consortium. - Alonso, Alvaro; Krijthe, Bouwe P; Aspelund, Thor; Stepas, Katherine A; Pencina, Michael J; Moser, Carlee B; Sinner, Moritz F; Sotoodehnia, Nona; Fontes, João D; Janssens, A Cecile J W; Kronmal, Richard A; Magnani, Jared W; et al. (J Am Heart Assoc, 2013)
BACKGROUND: Tools for the prediction of atrial fibrillation (AF) may identify high-risk individuals more likely to benefit from preventive interventions and serve as a benchmark to test novel putative risk factors. METHODS AND RESULTS: Individual-level data from 3 large cohorts in the United States (Atherosclerosis Risk in Communities [ARIC] study, the Cardiovascular Health Study [CHS], and the Framingham Heart Study [FHS]), including 18 556 men and women aged 46 to 94 years (19% African Americans, 81% whites) were pooled to derive predictive models for AF using clinical variables. Validation of the derived models was performed in 7672 participants from the Age, Gene and Environment-Reykjavik study (AGES) and the Rotterdam Study (RS). The analysis included 1186 incident AF cases in the derivation cohorts and 585 in the validation cohorts. A simple 5-year predictive model including the variables age, race, height, weight, systolic and diastolic blood pressure, current smoking, use of antihypertensive medication, diabetes, and history of myocardial infarction and heart failure had good discrimination (C-statistic, 0.765; 95% CI, 0.748 to 0.781). Addition of variables from the electrocardiogram did not improve the overall model discrimination (C-statistic, 0.767; 95% CI, 0.750 to 0.783; categorical net reclassification improvement, -0.0032; 95% CI, -0.0178 to 0.0113). In the validation cohorts, discrimination was acceptable (AGES C-statistic, 0.664; 95% CI, 0.632 to 0.697 and RS C-statistic, 0.705; 95% CI, 0.664 to 0.747) and calibration was adequate. CONCLUSION: A risk model including variables readily available in primary care settings adequately predicted AF in diverse populations from the United States and Europe.
Keywords: African Americans; Age Factors; Aged; Aged, 80 and over; Atrial Fibrillation; Cohort Studies; Diabetes Mellitus; European Continental Ancestry Group; Female; Heart Failure; Humans; Hypertension; Iceland; Incidence; Male; Middle Aged; Myocardial Infarction; Netherlands; Proportional Hazards Models; Risk Assessment; Smoking; United States

Soluble CD14: genomewide association analysis and relationship to cardiovascular risk and mortality in older adults. - Reiner, Alex P; Lange, Ethan M; Jenny, Nancy S; Chaves, Paulo H M; Ellis, Jaclyn; Li, Jin; Walston, Jeremy; Lange, Leslie A; Cushman, Mary; Tracy, Russell P (Arterioscler Thromb Vasc Biol, 2013)
OBJECTIVE: CD14 is a glycosylphosphotidylinositol-anchored membrane glycoprotein expressed on neutrophils and monocytes/macrophages that also circulates as a soluble form (sCD14). Despite the well-recognized role of CD14 in inflammation, relatively little is known about the genetic determinants of sCD14 or the relationship of sCD14 to vascular- and aging-related phenotypes. METHODS AND RESULTS: We measured baseline levels of sCD14 in >5000 European-American and black adults aged 65 years and older from the Cardiovascular Health Study, who were well characterized at baseline for atherosclerotic risk factors and subclinical cardiovascular disease, and who have been followed for clinical cardiovascular disease and mortality outcomes up to 20 years. At baseline, sCD14 generally showed strong positive correlations with traditional cardio-metabolic risk factors and with subclinical measures of vascular disease such as carotid wall thickness and ankle-brachial index (independently of traditional cardiovascular disease risk factors), and was also inversely correlated with body mass index. In genomewide association analyses of sCD14, we (1) confirmed the importance of the CD14 locus on chromosome 5q21 in European-American; (2) identified a novel African ancestry-specific allele of CD14 associated with lower sCD14 in blacks; and (3) identified a putative novel association in European-American of a nonsynonymous variant of PIGC, which encodes an enzyme required for the first step in glycosylphosphotidylinositol anchor biosynthesis. Finally, we show that, like other acute phase inflammatory biomarkers, sCD14 predicts incident cardiovascular disease, and strongly and independently predicts all-cause mortality in older adults. CONCLUSIONS: CD14 independently predicts risk mortality in older adults.
Keywords: African Americans; Age Factors; Aged; Biomarkers; Cardiovascular Diseases; Chromosomes, Human, Pair 5; European Continental Ancestry Group; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Haplotypes; Hexosyltransferases; Humans; Incidence; Inflammation Mediators; Linear Models; Lipopolysaccharide Receptors; Logistic Models; Male; Membrane Proteins; Multivariate Analysis; Phenotype; Polymorphism, Single Nucleotide; Principal Component Analysis; Prognosis; Proportional Hazards Models; Prospective Studies; Risk Assessment; Risk Factors; Time Factors; United States

Strategy to control type I error increases power to identify genetic variation using the full biological trajectory. - Benke, K S; Wu, Y; Fallin, D M; Maher, B; Palmer, L J (Genet Epidemiol, 2013)
Genome-wide association studies have been successful in identifying loci that underlie continuous traits measured at a single time point. To additionally consider continuous traits longitudinally, it is desirable to look at SNP effects at baseline and over time using linear-mixed effects models. Estimation and interpretation of two coefficients in the same model raises concern regarding the optimal control of type I error. To investigate this issue, we calculate type I error and power under an alternative for joint tests, including the two degree of freedom likelihood ratio test, and compare this to single degree of freedom tests for each effect separately at varying alpha levels. We show which joint tests are the optimal way to control the type I error and also illustrate that information can be gained by joint testing in situations where either or both SNP effects are underpowered. We also show that closed form power calculations can approximate simulated power for the case of balanced data, provide reasonable approximations for imbalanced data, but overestimate power for complicated residual error structures. We conclude that a two degree of freedom test is an attractive strategy in a hypothesis-free genome-wide setting and recommend its use for genome-wide studies employing linear-mixed effects models.
Keywords: Cohort Studies; Computer Simulation; Genetic Variation; Genome-Wide Association Study; Humans; Linear Models; Models, Genetic; Polymorphism, Single Nucleotide

A systematic mapping approach of 16q12.2/FTO and BMI in more than 20,000 African Americans narrows in on the underlying functional variation: results from the Population Architecture using Genomics and Epidemiology (PAGE) study. - Peters, Ulrike; North, Kari E; Sethupathy, Praveen; Buyske, Steve; Haessler, Jeff; Jiao, Shuo; Fesinmeyer, Megan D; Jackson, Rebecca D; Kuller, Lew H; Rajkovic, Aleksandar; Lim, Unhee; Cheng, Iona; et al. (PLoS Genet, 2013)
Genetic variants in intron 1 of the fat mass- and obesity-associated (FTO) gene have been consistently associated with body mass index (BMI) in Europeans. However, follow-up studies in African Americans (AA) have shown no support for some of the most consistently BMI-associated FTO index single nucleotide polymorphisms (SNPs). This is most likely explained by different race-specific linkage disequilibrium (LD) patterns and lower correlation overall in AA, which provides the opportunity to fine-map this region and narrow in on the functional variant. To comprehensively explore the 16q12.2/FTO locus and to search for second independent signals in the broader region, we fine-mapped a 646-kb region, encompassing the large FTO gene and the flanking gene RPGRIP1L by investigating a total of 3,756 variants (1,529 genotyped and 2,227 imputed variants) in 20,488 AAs across five studies. We observed associations between BMI and variants in the known FTO intron 1 locus: the SNP with the most significant p-value, rs56137030 (8.3 × 10(-6)) had not been highlighted in previous studies. While rs56137030was correlated at r(2)>0.5 with 103 SNPs in Europeans (including the GWAS index SNPs), this number was reduced to 28 SNPs in AA. Among rs56137030 and the 28 correlated SNPs, six were located within candidate intronic regulatory elements, including rs1421085, for which we predicted allele-specific binding affinity for the transcription factor CUX1, which has recently been implicated in the regulation of FTO. We did not find strong evidence for a second independent signal in the broader region. In summary, this large fine-mapping study in AA has substantially reduced the number of common alleles that are likely to be functional candidates of the known FTO locus. Importantly our study demonstrated that comprehensive fine-mapping in AA provides a powerful approach to narrow in on the functional candidate(s) underlying the initial GWAS findings in European populations.
Keywords: Adaptor Proteins, Signal Transducing; Adult; African Americans; Aged; Aged, 80 and over; Alleles; Body Mass Index; Chromosome Mapping; Continental Population Groups; European Continental Ancestry Group; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Linkage Disequilibrium; Male; Metagenomics; Middle Aged; Obesity; Proteins

Trans-ethnic fine-mapping of lipid loci identifies population-specific signals and allelic heterogeneity that increases the trait variance explained. - Wu, Ying; Waite, Lindsay L; Jackson, Anne U; Sheu, Wayne H-H; Buyske, Steven; Absher, Devin; Arnett, Donna K; Boerwinkle, Eric; Bonnycastle, Lori L; Carty, Cara L; Cheng, Iona; Cochran, Barbara; et al. (PLoS Genet, 2013)
Genome-wide association studies (GWAS) have identified ~100 loci associated with blood lipid levels, but much of the trait heritability remains unexplained, and at most loci the identities of the trait-influencing variants remain unknown. We conducted a trans-ethnic fine-mapping study at 18, 22, and 18 GWAS loci on the Metabochip for their association with triglycerides (TG), high-density lipoprotein cholesterol (HDL-C), and low-density lipoprotein cholesterol (LDL-C), respectively, in individuals of African American (n = 6,832), East Asian (n = 9,449), and European (n = 10,829) ancestry. We aimed to identify the variants with strongest association at each locus, identify additional and population-specific signals, refine association signals, and assess the relative significance of previously described functional variants. Among the 58 loci, 33 exhibited evidence of association at P<1 × 10(-4) in at least one ancestry group. Sequential conditional analyses revealed that ten, nine, and four loci in African Americans, Europeans, and East Asians, respectively, exhibited two or more signals. At these loci, accounting for all signals led to a 1.3- to 1.8-fold increase in the explained phenotypic variance compared to the strongest signals. Distinct signals across ancestry groups were identified at PCSK9 and APOA5. Trans-ethnic analyses narrowed the signals to smaller sets of variants at GCKR, PPP1R3B, ABO, LCAT, and ABCA1. Of 27 variants reported previously to have functional effects, 74% exhibited the strongest association at the respective signal. In conclusion, trans-ethnic high-density genotyping and analysis confirm the presence of allelic heterogeneity, allow the identification of population-specific variants, and limit the number of candidate SNPs for functional studies.
Keywords: African Americans; Apolipoproteins A; Cholesterol, HDL; Cholesterol, LDL; European Continental Ancestry Group; Genome-Wide Association Study; Humans; Lipoproteins, HDL; Lipoproteins, LDL; Proprotein Convertases; Serine Endopeptidases; Triglycerides

Use of antihypertensive medications and breast cancer risk. - Saltzman, Babette S; Weiss, Noel S; Sieh, Weiva; Fitzpatrick, Annette L; McTiernan, Anne; Daling, Janet R; Li, Christopher I (Cancer Causes Control, 2013)
PURPOSE: Use of specific antihypertensive medications (AHTs) has been hypothesized to increase breast cancer risk, but results across published studies are inconsistent. METHODS: We re-evaluated the relationship between AHT use and breast cancer risk in a prospective cohort of 3,201 women ≥65 years of age at recruitment now with more than double the length of follow-up (12 vs. 5 years) and substantially more breast cancer diagnoses (188 compared with 75 cases). We estimated the association between AHT use overall as well as use of specific formulations (based on data collected annually) and breast cancer risk using multivariate-adjusted Cox regression. RESULTS: Compared with women who reported no use of AHTs, women who had used calcium channel blockers (CCB) within the past two years had a 1.6-fold increased risk of breast cancer (95 % confidence interval (CI): 1.0-2.5), and in particular, recent users of immediate-release CCBs had a 2.4-fold increased risk (95 % CI: 1.3-4.5). Neither ever nor recent use of any other type of AHT was associated with breast cancer risk. CONCLUSIONS: While the observed association between immediate-release CCBs and breast cancer risk is based on a small sample size and needs to be interpreted cautiously, this result is consistent with others in the literature. However, given declines in use of these preparations in favor of sustained-release CCBs, which was not related to risk, the potential clinical and public health impact of this association is limited. This study also adds to the evidence that other commonly used AHTs are not strongly related to breast cancer risk.
Keywords: Aged; Aged, 80 and over; Antihypertensive Agents; Breast Neoplasms; Cohort Studies; Female; Humans; Proportional Hazards Models; Prospective Studies; Risk Factors; United States

ADAM19 and HTR4 variants and pulmonary function: Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) Consortium Targeted Sequencing Study. - London, Stephanie J; Gao, Wei; Gharib, Sina A; Hancock, Dana B; Wilk, Jemma B; House, John S; Gibbs, Richard A; Muzny, Donna M; Lumley, Thomas; Franceschini, Nora; North, Kari E; Psaty, Bruce M; et al. (Circ Cardiovasc Genet, 2014)
BACKGROUND: The pulmonary function measures of forced expiratory volume in 1 second (FEV1) and its ratio to forced vital capacity (FVC) are used in the diagnosis and monitoring of lung diseases and predict cardiovascular mortality in the general population. Genome-wide association studies (GWASs) have identified numerous loci associated with FEV1 and FEV1/FVC, but the causal variants remain uncertain. We hypothesized that novel or rare variants poorly tagged by GWASs may explain the significant associations between FEV1/FVC and 2 genes: ADAM19 and HTR4. METHODS AND RESULTS: We sequenced ADAM19 and its promoter region along with the ≈21-kb portion of HTR4 harboring GWAS single-nucleotide polymorphisms for pulmonary function and analyzed associations with FEV1/FVC among 3983 participants of European ancestry from Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) Consortium. Meta-analysis of common variants in each region identified statistically significant associations (316 tests; P<1.58×10(-4)) with FEV1/FVC for 14 ADAM19 single-nucleotide polymorphisms and 24 HTR4 single-nucleotide polymorphisms. After conditioning on the sentinel GWASs hit in each gene (ADAM19 rs1422795, minor allele frequency=0.33 and HTR4 rs11168048, minor allele frequency=0.40], 1 single-nucleotide polymorphism remained statistically significant (ADAM19 rs13155908, minor allele frequency=0.12; P=1.56×10(-4)). Analysis of rare variants (minor allele frequency <1%) using sequence kernel association test did not identify associations with either region. CONCLUSIONS: Sequencing identified 1 common variant associated with FEV1/FVC independent of the sentinel ADAM19 GWAS hit and supports the original HTR4 GWAS findings. Rare variants do not seem to underlie GWAS associations with pulmonary function for common variants in ADAM19 and HTR4.
Keywords: ADAM Proteins; Aged; Aged, 80 and over; Aging; Cohort Studies; Female; Genetic Variation; Genome-Wide Association Study; Genomics; Heart Diseases; Humans; Lung; Male; Middle Aged; Polymorphism, Single Nucleotide; Sequence Analysis, DNA

Association between alcohol and cardiovascular disease: Mendelian randomisation analysis based on individual participant data. - Holmes, Michael V; Dale, Caroline E; Zuccolo, Luisa; Silverwood, Richard J; Guo, Yiran; Ye, Zheng; Prieto-Merino, David; Dehghan, Abbas; Trompet, Stella; Wong, Andrew; Cavadino, Alana; Drogan, Dagmar; et al. (BMJ, 2014)
OBJECTIVE: To use the rs1229984 variant in the alcohol dehydrogenase 1B gene (ADH1B) as an instrument to investigate the causal role of alcohol in cardiovascular disease. DESIGN: Mendelian randomisation meta-analysis of 56 epidemiological studies. PARTICIPANTS: 261 991 individuals of European descent, including 20 259 coronary heart disease cases and 10 164 stroke events. Data were available on ADH1B rs1229984 variant, alcohol phenotypes, and cardiovascular biomarkers. MAIN OUTCOME MEASURES: Odds ratio for coronary heart disease and stroke associated with the ADH1B variant in all individuals and by categories of alcohol consumption. RESULTS: Carriers of the A-allele of ADH1B rs1229984 consumed 17.2% fewer units of alcohol per week (95% confidence interval 15.6% to 18.9%), had a lower prevalence of binge drinking (odds ratio 0.78 (95% CI 0.73 to 0.84)), and had higher abstention (odds ratio 1.27 (1.21 to 1.34)) than non-carriers. Rs1229984 A-allele carriers had lower systolic blood pressure (-0.88 (-1.19 to -0.56) mm Hg), interleukin-6 levels (-5.2% (-7.8 to -2.4%)), waist circumference (-0.3 (-0.6 to -0.1) cm), and body mass index (-0.17 (-0.24 to -0.10) kg/m(2)). Rs1229984 A-allele carriers had lower odds of coronary heart disease (odds ratio 0.90 (0.84 to 0.96)). The protective association of the ADH1B rs1229984 A-allele variant remained the same across all categories of alcohol consumption (P=0.83 for heterogeneity). Although no association of rs1229984 was identified with the combined subtypes of stroke, carriers of the A-allele had lower odds of ischaemic stroke (odds ratio 0.83 (0.72 to 0.95)). CONCLUSIONS: Individuals with a genetic variant associated with non-drinking and lower alcohol consumption had a more favourable cardiovascular profile and a reduced risk of coronary heart disease than those without the genetic variant. This suggests that reduction of alcohol consumption, even for light to moderate drinkers, is beneficial for cardiovascular health.
Keywords: Adult; Aged; Alcohol Dehydrogenase; Alcohol Drinking; Biomarkers; Coronary Disease; Female; Genetic Markers; Genotype; Humans; Male; Mendelian Randomization Analysis; Middle Aged; Models, Statistical; Polymorphism, Single Nucleotide; Stroke

Association of kidney disease measures with ischemic versus hemorrhagic strokes: pooled analyses of 4 prospective community-based cohorts. - Mahmoodi, Bakhtawar K; Yatsuya, Hiroshi; Matsushita, Kunihiro; Sang, Yinying; Gottesman, Rebecca F; Astor, Brad C; Woodward, Mark; Longstreth, W T; Psaty, Bruce M; Shlipak, Michael G; Folsom, Aaron R; Gansevoort, Ron T; et al. (Stroke, 2014)
BACKGROUND AND PURPOSE: Although low glomerular filtration rate (GFR) and albuminuria are associated with increased risk of stroke, few studies compared their contribution to risk of ischemic versus hemorrhagic stroke separately. We contrasted the association of these kidney measures with ischemic versus hemorrhagic stroke. METHODS: We pooled individual participant data from 4 community-based cohorts: 3 from the United States and 1 from The Netherlands. GFR was estimated using both creatinine and cystatin C, and albuminuria was quantified by urinary albumin-to-creatinine ratio (ACR). Associations of estimated GFR and ACR were compared for each stroke type (ischemic versus intraparenchymal hemorrhagic) using study-stratified Cox regression. RESULTS: Among 29,595 participants (mean age, 61 [SD 12.5] years; 46% men; 17% black), 1261 developed stroke (12% hemorrhagic) during 280,549 person-years. Low estimated GFR was significantly associated with increased risk of ischemic stroke, but not hemorrhagic stroke, whereas high ACR was associated with both stroke types. Adjusted hazard ratios for ischemic and hemorrhagic stroke at estimated GFR of 45 (versus 95) mL/min per 1.73 m2 were 1.30 (95% confidence interval, 1.01-1.68) and 0.92 (0.47-1.81), respectively. In contrast, the corresponding hazard ratios for ACR of 300 (versus 5) mg/g were 1.62 (1.27-2.07) for ischemic and 2.57 (1.37-4.83) for hemorrhagic stroke, with significantly stronger association with hemorrhagic stroke (P=0.04). For hemorrhagic stroke, the association of elevated ACR was of similar magnitude as that of elevated systolic blood pressure. CONCLUSIONS: Whereas albuminuria showed significant association with both stroke types, the association of decreased estimated GFR was only significant for ischemic stroke. The strong association of albuminuria with both stroke types warrants clinical attention and further investigations.
Keywords: Aged; Albuminuria; Brain Ischemia; Comorbidity; Female; Glomerular Filtration Rate; Humans; Intracranial Hemorrhages; Kidney Diseases; Male; Middle Aged; Netherlands; Proportional Hazards Models; Prospective Studies; Risk Factors; Stroke; United States

Association of levels of fasting glucose and insulin with rare variants at the chromosome 11p11.2-MADD locus: Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) Consortium Targeted Sequencing Study. - Cornes, Belinda K; Brody, Jennifer A; Nikpoor, Naghmeh; Morrison, Alanna C; Chu, Huan; Ahn, Byung Soo; Wang, Shuai; Dauriz, Marco; Barzilay, Joshua I; Dupuis, Josée; Florez, Jose C; Coresh, Josef; et al. (Circ Cardiovasc Genet, 2014)
BACKGROUND: Common variation at the 11p11.2 locus, encompassing MADD, ACP2, NR1H3, MYBPC3, and SPI1, has been associated in genome-wide association studies with fasting glucose and insulin (FI). In the Cohorts for Heart and Aging Research in Genomic Epidemiology Targeted Sequencing Study, we sequenced 5 gene regions at 11p11.2 to identify rare, potentially functional variants influencing fasting glucose or FI levels. METHODS AND RESULTS: Sequencing (mean depth, 38×) across 16.1 kb in 3566 individuals without diabetes mellitus identified 653 variants, 79.9% of which were rare (minor allele frequency <1%) and novel. We analyzed rare variants in 5 gene regions with FI or fasting glucose using the sequence kernel association test. At NR1H3, 53 rare variants were jointly associated with FI (P=2.73×10(-3)); of these, 7 were predicted to have regulatory function and showed association with FI (P=1.28×10(-3)). Conditioning on 2 previously associated variants at MADD (rs7944584, rs10838687) did not attenuate this association, suggesting that there are >2 independent signals at 11p11.2. One predicted regulatory variant, chr11:47227430 (hg18; minor allele frequency=0.00068), contributed 20.6% to the overall sequence kernel association test score at NR1H3, lies in intron 2 of NR1H3, and is a predicted binding site for forkhead box A1 (FOXA1), a transcription factor associated with insulin regulation. In human HepG2 hepatoma cells, the rare chr11:47227430 A allele disrupted FOXA1 binding and reduced FOXA1-dependent transcriptional activity. CONCLUSIONS: Sequencing at 11p11.2-NR1H3 identified rare variation associated with FI. One variant, chr11:47227430, seems to be functional, with the rare A allele reducing transcription factor FOXA1 binding and FOXA1-dependent transcriptional activity.
Keywords: Aged; Aged, 80 and over; Aging; Blood Glucose; Chromosomes, Human, Pair 11; Cohort Studies; Death Domain Receptor Signaling Adaptor Proteins; Diabetes Mellitus, Type 2; Fasting; Female; Gene Frequency; Genetic Variation; Genome-Wide Association Study; Genomics; Guanine Nucleotide Exchange Factors; Heart Diseases; Humans; Insulin; Male; Middle Aged; Polymorphism, Single Nucleotide; Sequence Analysis, DNA

Association of low-frequency and rare coding-sequence variants with blood lipids and coronary heart disease in 56,000 whites and blacks. - Peloso, Gina M; Auer, Paul L; Bis, Joshua C; Voorman, Arend; Morrison, Alanna C; Stitziel, Nathan O; Brody, Jennifer A; Khetarpal, Sumeet A; Crosby, Jacy R; Fornage, Myriam; Isaacs, Aaron; Jakobsdottir, Johanna; et al. (Am J Hum Genet, 2014)
Low-frequency coding DNA sequence variants in the proprotein convertase subtilisin/kexin type 9 gene (PCSK9) lower plasma low-density lipoprotein cholesterol (LDL-C), protect against risk of coronary heart disease (CHD), and have prompted the development of a new class of therapeutics. It is uncertain whether the PCSK9 example represents a paradigm or an isolated exception. We used the "Exome Array" to genotype >200,000 low-frequency and rare coding sequence variants across the genome in 56,538 individuals (42,208 European ancestry [EA] and 14,330 African ancestry [AA]) and tested these variants for association with LDL-C, high-density lipoprotein cholesterol (HDL-C), and triglycerides. Although we did not identify new genes associated with LDL-C, we did identify four low-frequency (frequencies between 0.1% and 2%) variants (ANGPTL8 rs145464906 [c.361C>T; p.Gln121*], PAFAH1B2 rs186808413 [c.482C>T; p.Ser161Leu], COL18A1 rs114139997 [c.331G>A; p.Gly111Arg], and PCSK7 rs142953140 [c.1511G>A; p.Arg504His]) with large effects on HDL-C and/or triglycerides. None of these four variants was associated with risk for CHD, suggesting that examples of low-frequency coding variants with robust effects on both lipids and CHD will be limited.
Keywords: 1-Alkyl-2-acetylglycerophosphocholine Esterase; Adult; African Continental Ancestry Group; Aged; Alleles; Animals; Cholesterol, HDL; Cholesterol, LDL; Cohort Studies; Coronary Disease; European Continental Ancestry Group; Female; Gene Frequency; Genetic Association Studies; Genetic Code; Genetic Variation; Humans; Linear Models; Male; Mice; Mice, Inbred C57BL; Microtubule-Associated Proteins; Middle Aged; Phenotype; Sequence Analysis, DNA; Subtilisins; Triglycerides

Associations of NINJ2 sequence variants with incident ischemic stroke in the Cohorts for Heart and Aging in Genomic Epidemiology (CHARGE) consortium. - Bis, Joshua C; DeStefano, Anita; Liu, Xiaoming; Brody, Jennifer A; Choi, Seung Hoan; Verhaaren, Benjamin F J; Debette, Stephanie; Ikram, M Arfan; Shahar, Eyal; Butler, Kenneth R; Gottesman, Rebecca F; Muzny, Donna; et al. (PLoS One, 2014)
BACKGROUND: Stroke, the leading neurologic cause of death and disability, has a substantial genetic component. We previously conducted a genome-wide association study (GWAS) in four prospective studies from the Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) consortium and demonstrated that sequence variants near the NINJ2 gene are associated with incident ischemic stroke. Here, we sought to fine-map functional variants in the region and evaluate the contribution of rare variants to ischemic stroke risk. METHODS AND RESULTS: We sequenced 196 kb around NINJ2 on chromosome 12p13 among 3,986 European ancestry participants, including 475 ischemic stroke cases, from the Atherosclerosis Risk in Communities Study, Cardiovascular Health Study, and Framingham Heart Study. Meta-analyses of single-variant tests for 425 common variants (minor allele frequency [MAF] ≥ 1%) confirmed the original GWAS results and identified an independent intronic variant, rs34166160 (MAF = 0.012), most significantly associated with incident ischemic stroke (HR = 1.80, p = 0.0003). Aggregating 278 putatively-functional variants with MAF≤ 1% using count statistics, we observed a nominally statistically significant association, with the burden of rare NINJ2 variants contributing to decreased ischemic stroke incidence (HR = 0.81; p = 0.026). CONCLUSION: Common and rare variants in the NINJ2 region were nominally associated with incident ischemic stroke among a subset of CHARGE participants. Allelic heterogeneity at this locus, caused by multiple rare, low frequency, and common variants with disparate effects on risk, may explain the difficulties in replicating the original GWAS results. Additional studies that take into account the complex allelic architecture at this locus are needed to confirm these findings.
Keywords: Cell Adhesion Molecules, Neuronal; European Continental Ancestry Group; Female; Genetic Association Studies; Genetic Heterogeneity; Humans; Introns; Ischemia; Male; Myocardial Infarction; Polymorphism, Single Nucleotide; Prospective Studies; Sequence Analysis, DNA

B-type natriuretic peptide and C-reactive protein in the prediction of atrial fibrillation risk: the CHARGE-AF Consortium of community-based cohort studies. - Sinner, Moritz F; Stepas, Katherine A; Moser, Carlee B; Krijthe, Bouwe P; Aspelund, Thor; Sotoodehnia, Nona; Fontes, João D; Janssens, A Cecile J W; Kronmal, Richard A; Magnani, Jared W; Witteman, Jacqueline C; Chamberlain, Alanna M; et al. (Europace, 2014)
AIMS: B-type natriuretic peptide (BNP) and C-reactive protein (CRP) predict atrial fibrillation (AF) risk. However, their risk stratification abilities in the broad community remain uncertain. We sought to improve risk stratification for AF using biomarker information. METHODS AND RESULTS: We ascertained AF incidence in 18 556 Whites and African Americans from the Atherosclerosis Risk in Communities Study (ARIC, n=10 675), Cardiovascular Health Study (CHS, n = 5043), and Framingham Heart Study (FHS, n = 2838), followed for 5 years (prediction horizon). We added BNP (ARIC/CHS: N-terminal pro-B-type natriuretic peptide; FHS: BNP), CRP, or both to a previously reported AF risk score, and assessed model calibration and predictive ability [C-statistic, integrated discrimination improvement (IDI), and net reclassification improvement (NRI)]. We replicated models in two independent European cohorts: Age, Gene/Environment Susceptibility Reykjavik Study (AGES), n = 4467; Rotterdam Study (RS), n = 3203. B-type natriuretic peptide and CRP were significantly associated with AF incidence (n = 1186): hazard ratio per 1-SD ln-transformed biomarker 1.66 [95% confidence interval (CI), 1.56-1.76], P < 0.0001 and 1.18 (95% CI, 1.11-1.25), P < 0.0001, respectively. Model calibration was sufficient (BNP, χ(2) = 17.0; CRP, χ(2) = 10.5; BNP and CRP, χ(2) = 13.1). B-type natriuretic peptide improved the C-statistic from 0.765 to 0.790, yielded an IDI of 0.027 (95% CI, 0.022-0.032), a relative IDI of 41.5%, and a continuous NRI of 0.389 (95% CI, 0.322-0.455). The predictive ability of CRP was limited (C-statistic increment 0.003). B-type natriuretic peptide consistently improved prediction in AGES and RS. CONCLUSION: B-type natriuretic peptide, not CRP, substantially improved AF risk prediction beyond clinical factors in an independently replicated, heterogeneous population. B-type natriuretic peptide may serve as a benchmark to evaluate novel putative AF risk biomarkers.
Keywords: Aged; Atrial Fibrillation; Biomarkers; C-Reactive Protein; Europe; Female; Humans; Incidence; Male; Natriuretic Peptide, Brain; Peptide Fragments; Predictive Value of Tests; Risk Assessment; Risk Factors; United States

The challenges of genome-wide interaction studies: lessons to learn from the analysis of HDL blood levels. - van Leeuwen, Elisabeth M; Smouter, Françoise A S; Kam-Thong, Tony; Karbalai, Nazanin; Smith, Albert V; Harris, Tamara B; Launer, Lenore J; Sitlani, Colleen M; Li, Guo; Brody, Jennifer A; Bis, Joshua C; White, Charles C; et al. (PLoS One, 2014)
Genome-wide association studies (GWAS) have revealed 74 single nucleotide polymorphisms (SNPs) associated with high-density lipoprotein cholesterol (HDL) blood levels. This study is, to our knowledge, the first genome-wide interaction study (GWIS) to identify SNP×SNP interactions associated with HDL levels. We performed a GWIS in the Rotterdam Study (RS) cohort I (RS-I) using the GLIDE tool which leverages the massively parallel computing power of Graphics Processing Units (GPUs) to perform linear regression on all genome-wide pairs of SNPs. By performing a meta-analysis together with Rotterdam Study cohorts II and III (RS-II and RS-III), we were able to filter 181 interaction terms with a p-value<1 · 10-8 that replicated in the two independent cohorts. We were not able to replicate any of these interaction term in the AGES, ARIC, CHS, ERF, FHS and NFBC-66 cohorts (Ntotal = 30,011) when adjusting for multiple testing. Our GWIS resulted in the consistent finding of a possible interaction between rs774801 in ARMC8 (ENSG00000114098) and rs12442098 in SPATA8 (ENSG00000185594) being associated with HDL levels. However, p-values do not reach the preset Bonferroni correction of the p-values. Our study suggest that even for highly genetically determined traits such as HDL the sample sizes needed to detect SNP×SNP interactions are large and the 2-step filtering approaches do not yield a solution. Here we present our analysis plan and our reservations concerning GWIS.
Keywords: Cholesterol, HDL; Female; Genome-Wide Association Study; Humans; Male; Middle Aged; Polymorphism, Single Nucleotide

Common variation in fatty acid metabolic genes and risk of incident sudden cardiac arrest. - Lemaitre, Rozenn N; Johnson, Catherine O; Hesselson, Stephanie; Sotoodehnia, Nona; Sotoodhenia, Nona; McKnight, Barbara; Sitlani, Colleen M; Rea, Thomas D; King, Irena B; Kwok, Pui-Yan; Mak, Angel; Li, Guo; et al. (Heart Rhythm, 2014)
BACKGROUND: There is limited information on genetic factors associated with sudden cardiac arrest (SCA). OBJECTIVE: To assess the association of common variation in genes in fatty acid pathways with SCA risk. METHODS: We selected 85 candidate genes and 1155 single nucleotide polymorphisms (SNPs) tagging common variation in each gene. We investigated the SNP associations with SCA in a population-based case-control study. Cases (n = 2160) were from a repository of SCA in the greater Seattle area. Controls (n = 2615), frequency-matched on age and sex, were from the same area. We used linear logistic regression to examine SNP associations with SCA. We performed permutation-based p-min tests to account for multiple comparisons within each gene. The SNP associations with a corrected P value of <.05 were then examined in a meta-analysis of these SNP associations in 9 replication studies totaling 2129 SCA cases and 23,833 noncases. RESULTS: Eight SNPs in or near 8 genes were associated with SCA risk in the discovery study, one of which was nominally significant in the replication phase (rs7737692, minor allele frequency 36%, near the LPCAT1 gene). For each copy of the minor allele, rs7737692 was associated with 13% lower SCA risk (95% confidence interval -21% to -5%) in the discovery phase and 9% lower SCA risk (95% confidence interval -16% to -1%) in the replication phase. CONCLUSIONS: While none of the associations reached significance with Bonferroni correction, a common genetic variant near LPCAT1, a gene involved in the remodeling of phospholipids, was nominally associated with incident SCA risk. Further study is needed to validate this observation.
Keywords: 1-Acylglycerophosphocholine O-Acyltransferase; Aged; Algorithms; Alleles; Case-Control Studies; Death, Sudden, Cardiac; Fatty Acids; Female; Genetic Predisposition to Disease; Genetic Variation; Genotype; Humans; Male; Polymorphism, Single Nucleotide; Risk Factors

Coronary heart disease risks associated with high levels of HDL cholesterol. - Wilkins, John T; Ning, Hongyan; Stone, Neil J; Criqui, Michael H; Zhao, Lihui; Greenland, Philip; Lloyd-Jones, Donald M (J Am Heart Assoc, 2014)
BACKGROUND: The association between high-density lipoprotein cholesterol (HDL-C) and coronary heart disease (CHD) events is not well described in individuals with very high levels of HDL-C (>80 mg/dL). METHODS AND RESULTS: Using pooled data from 6 community-based cohorts we examined CHD and total mortality risks across a broad range of HDL-C, including values in excess of 80 mg/dL. We used Cox proportional hazards models with penalized splines to assess multivariable, adjusted, sex-stratified associations of HDL-C with the hazard for CHD events and total mortality, using HDL-C 45 mg/dL and 55 mg/dL as the referent in men and women, respectively. Analyses included 11 515 men and 12 925 women yielding 307 245 person-years of follow-up. In men, the association between HDL-C and CHD events was inverse and linear across most HDL-C values; however at HDL-C values >90 mg/dL there was a plateau effect in the pattern of association. In women, the association between HDL-C and CHD events was inverse and linear across lower values of HDL-C, however at HDL-C values >75 mg/dL there were no further reductions in the hazard ratio point estimates for CHD. In unadjusted models there were increased total mortality risks in men with very high HDL-C, however mortality risks observed in participants with very high HDL-C were attenuated after adjustment for traditional risk factors. CONCLUSIONS: We did not observe further reductions in CHD risk with HDL-C values higher than 90 mg/dL in men and 75 mg/dL in women.
Keywords: Aged; Biomarkers; Cholesterol, HDL; Coronary Disease; Female; Humans; Linear Models; Male; Middle Aged; Multivariate Analysis; Prognosis; Proportional Hazards Models; Risk Assessment; Risk Factors; Time Factors; United States; Up-Regulation

Decline in estimated glomerular filtration rate and subsequent risk of end-stage renal disease and mortality. - Coresh, Josef; Turin, Tanvir Chowdhury; Matsushita, Kunihiro; Sang, Yingying; Ballew, Shoshana H; Appel, Lawrence J; Arima, Hisatomi; Chadban, Steven J; Cirillo, Massimo; Djurdjev, Ognjenka; Green, Jamie A; Heine, Gunnar H; et al. (JAMA, 2014)
IMPORTANCE: The established chronic kidney disease (CKD) progression end point of end-stage renal disease (ESRD) or a doubling of serum creatinine concentration (corresponding to a change in estimated glomerular filtration rate [GFR] of −57% or greater) is a late event. OBJECTIVE: To characterize the association of decline in estimated GFR with subsequent progression to ESRD with implications for using lesser declines in estimated GFR as potential alternative end points for CKD progression. Because most people with CKD die before reaching ESRD, mortality risk also was investigated. DATA SOURCES AND STUDY SELECTION: Individual meta-analysis of 1.7 million participants with 12,344 ESRD events and 223,944 deaths from 35 cohorts in the CKD Prognosis Consortium with a repeated measure of serum creatinine concentration over 1 to 3 years and outcome data. DATA EXTRACTION AND SYNTHESIS: Transfer of individual participant data or standardized analysis of outputs for random-effects meta-analysis conducted between July 2012 and September 2013, with baseline estimated GFR values collected from 1975 through 2012. MAIN OUTCOMES AND MEASURES: End-stage renal disease (initiation of dialysis or transplantation) or all-cause mortality risk related to percentage change in estimated GFR over 2 years, adjusted for potential confounders and first estimated GFR. RESULTS: The adjusted hazard ratios (HRs) of ESRD and mortality were higher with larger estimated GFR decline. Among participants with baseline estimated GFR of less than 60 mL/min/1.73 m2, the adjusted HRs for ESRD were 32.1 (95% CI, 22.3-46.3) for changes of −57% in estimated GFR and 5.4 (95% CI, 4.5-6.4) for changes of −30%. However, changes of −30% or greater (6.9% [95% CI, 6.4%-7.4%] of the entire consortium) were more common than changes of −57% (0.79% [95% CI, 0.52%-1.06%]). This association was strong and consistent across the length of the baseline period (1 to 3 years), baseline estimated GFR, age, diabetes status, or albuminuria. Average adjusted 10-year risk of ESRD (in patients with a baseline estimated GFR of 35 mL/min/1.73 m2) was 99% (95% CI, 95%-100%) for estimated GFR change of −57%, was 83% (95% CI, 71%-93%) for estimated GFR change of −40%, and was 64% (95% CI, 52%-77%) for estimated GFR change of −30% vs 18% (95% CI, 15%-22%) for estimated GFR change of 0%. Corresponding mortality risks were 77% (95% CI, 71%-82%), 60% (95% CI, 56%-63%), and 50% (95% CI, 47%-52%) vs 32% (95% CI, 31%-33%), showing a similar but weaker pattern. CONCLUSIONS AND RELEVANCE: Declines in estimated GFR smaller than a doubling of serum creatinine concentration occurred more commonly and were strongly and consistently associated with the risk of ESRD and mortality, supporting consideration of lesser declines in estimated GFR (such as a 30% reduction over 2 years) as an alternative end point for CKD progression.
Keywords: Adult; Aged; Aged, 80 and over; Cohort Studies; Creatinine; Disease Progression; Endpoint Determination; Female; Glomerular Filtration Rate; Humans; Kidney Failure, Chronic; Male; Middle Aged; Reference Values; Risk

Development and validation of a brief dementia screening indicator for primary care. - Barnes, Deborah E; Beiser, Alexa S; Lee, Anne; Langa, Kenneth M; Koyama, Alain; Preis, Sarah R; Neuhaus, John; McCammon, Ryan J; Yaffe, Kristine; Seshadri, Sudha; Haan, Mary N; Weir, David R (Alzheimers Dement, 2014)
BACKGROUND: Detection of "any cognitive impairment" is mandated as part of the Medicare annual wellness visit, but screening all patients may result in excessive false positives. METHODS: We developed and validated a brief Dementia Screening Indicator using data from four large, ongoing cohort studies (the Cardiovascular Health Study [CHS]; the Framingham Heart Study [FHS]; the Health and Retirement Study [HRS]; the Sacramento Area Latino Study on Aging [SALSA]) to help clinicians identify a subgroup of high-risk patients to target for cognitive screening. RESULTS: The final Dementia Screening Indicator included age (1 point/year; ages, 65-79 years), less than 12 years of education (9 points), stroke (6 points), diabetes mellitus (3 points), body mass index less than 18.5 kg/m(2) (8 points), requiring assistance with money or medications (10 points), and depressive symptoms (6 points). Accuracy was good across the cohorts (Harrell's C statistic: CHS, 0.68; FHS, 0.77; HRS, 0.76; SALSA, 0.78). CONCLUSIONS: The Dementia Screening Indicator is a simple tool that may be useful in primary care settings to identify high-risk patients to target for cognitive screening.
Keywords: Aged; Cohort Studies; Dementia; Female; Humans; Male; Mass Screening; Predictive Value of Tests; Primary Health Care; Proportional Hazards Models; Risk Assessment

Development and validation of an ankle brachial index risk model for the prediction of cardiovascular events. - Fowkes, F G R; Murray, G D; Butcher, I; Folsom, A R; Hirsch, A T; Couper, D J; deBacker, G; Kornitzer, M; Newman, A B; Sutton-Tyrrell, K C; Cushman, M; Lee, A J; et al. (Eur J Prev Cardiol, 2014)
BACKGROUND: The ankle brachial index (ABI) is related to risk of cardiovascular events independent of the Framingham risk score (FRS). The aim of this study was to develop and evaluate a risk model for cardiovascular events incorporating the ABI and FRS. DESIGN: An analysis of participant data from 18 cohorts in which 24,375 men and 20,377 women free of coronary heart disease had ABI measured and were followed up for events. METHODS: Subjects were divided into a development and internal validation dataset and an external validation dataset. Two models, comprising FRS and FRS + ABI, were fitted for the primary outcome of major coronary events. RESULTS: In predicting events in the external validation dataset, C-index for the FRS was 0.672 (95% CI 0.599 to 0.737) in men and 0.578 (95% CI 0.492 to 0.661) in women. The FRS + ABI led to a small increase in C-index in men to 0.685 (95% CI 0.612 to 0.749) and large increase in women to 0.690 (95% CI 0.605 to 0.764) with net reclassification improvement (NRI) of 4.3% (95% CI 0.0 to 7.6%, p = 0.050) and 9.6% (95% CI 6.1 to 16.4%, p < 0.001), respectively. Restricting the FRS + ABI model to those with FRS intermediate 10-year risk of 10 to 19% resulted in higher NRI of 15.9% (95% CI 6.1 to 20.6%, p < 0.001) in men and 23.3% (95% CI 13.8 to 62.5%, p = 0.002) in women. However, incorporating ABI in an improved newly fitted risk factor model had a nonsignificant effect: NRI 2.0% (95% CI 2.3 to 4.2%, p = 0.567) in men and 1.1% (95% CI 1.9 to 4.0%, p = 0.483) in women. CONCLUSIONS: An ABI risk model may improve prediction especially in individuals at intermediate risk and when performance of the base risk factor model is modest.
Keywords: Adult; Aged; Aged, 80 and over; Ankle Brachial Index; Cardiovascular Diseases; Europe; European Continental Ancestry Group; Female; Humans; Male; Middle Aged; Models, Statistical; Predictive Value of Tests; Prognosis; Reproducibility of Results; Risk Assessment; Risk Factors; Sex Factors; Time Factors; United States; Young Adult

Disability and recovery of independent function in obstructive lung disease: the cardiovascular health study. - Fan, Vincent S; Locke, Emily R; Diehr, Paula; Wilsdon, Anthony; Enright, Paul; Yende, Sachin; Avdalovic, Mark; Barr, Graham; Kapur, Vishesh K; Thomas, Rachel; Krishnan, Jerry A; Lovasi, Gina; et al. (Respiration, 2014)
BACKGROUND: Chronic obstructive lung disease frequently leads to disability. Older patients may experience transitions between states of disability and independence over time. OBJECTIVE: To identify factors associated with transition between states of disability and independent function in obstructive lung disease. METHODS: We analyzed data on 4,394 participants in the Cardiovascular Health Study who completed prebronchodilator spirometry. We calculated the 1-year probability of developing and resolving impairment in ≥1 instrumental activity of daily living (IADL) or ≥1 activity of daily living (ADL) using transition probability analysis. We identified factors associated with resolving disability using relative risk (RR) regression. RESULTS: The prevalence of IADL impairment was higher with moderate (23.9%) and severe (36.9%) airflow obstruction compared to normal spirometry (22.5%; p < 0.001). Among participants with severe airflow obstruction, 23.5% recovered independence in IADLs and 40.5% recovered independence in ADLs. In the adjusted analyses, airflow obstruction predicted the development of IADL, but not ADL impairment. Participants with severe airflow obstruction were less likely to resolve IADL impairment [RR 0.67 and 95% confidence interval (CI) 0.49-0.94]. Compared to the most active individuals (i.e. who walked ≥28 blocks per week), walking less was associated with a decreased likelihood of resolving IADL impairment (7-27 blocks: RR 0.81 and 95% CI 0.69-0.86 and <7 blocks: RR 0.73 and 95% CI 0.61-0.86). Increased strength (RR 1.16 and 95% CI 1.05-1.29) was associated with resolving IADL impairment. CONCLUSIONS: Disability is common in older people, especially in those with severe airflow obstruction. Increased physical activity and muscle strength are associated with recovery. Research is needed on interventions to improve these factors among patients with obstructive lung disease and disability.
Keywords: Activities of Daily Living; Aged; Cardiac Rehabilitation; Cardiovascular Diseases; Disability Evaluation; Exercise Test; Female; Humans; Independent Living; Longitudinal Studies; Male; Motor Activity; Muscle Strength; Outcome Assessment (Health Care); Pulmonary Disease, Chronic Obstructive; Recovery of Function; Risk Assessment; Severity of Illness Index; Spirometry; United States

Drug-gene interactions and the search for missing heritability: a cross-sectional pharmacogenomics study of the QT interval. - Avery, C L; Sitlani, C M; Arking, D E; Arnett, D K; Bis, J C; Boerwinkle, E; Buckley, B M; Ida Chen, Y-D; de Craen, A J M; Eijgelsheim, M; Enquobahrie, D; Evans, D S; et al. (Pharmacogenomics J, 2014)
Variability in response to drug use is common and heritable, suggesting that genome-wide pharmacogenomics studies may help explain the 'missing heritability' of complex traits. Here, we describe four independent analyses in 33 781 participants of European ancestry from 10 cohorts that were designed to identify genetic variants modifying the effects of drugs on QT interval duration (QT). Each analysis cross-sectionally examined four therapeutic classes: thiazide diuretics (prevalence of use=13.0%), tri/tetracyclic antidepressants (2.6%), sulfonylurea hypoglycemic agents (2.9%) and QT-prolonging drugs as classified by the University of Arizona Center for Education and Research on Therapeutics (4.4%). Drug-gene interactions were estimated using covariable-adjusted linear regression and results were combined with fixed-effects meta-analysis. Although drug-single-nucleotide polymorphism (SNP) interactions were biologically plausible and variables were well-measured, findings from the four cross-sectional meta-analyses were null (Pinteraction>5.0 × 10(-8)). Simulations suggested that additional efforts, including longitudinal modeling to increase statistical power, are likely needed to identify potentially important pharmacogenomic effects.
Keywords: Computer Simulation; Cross-Sectional Studies; Drug-Related Side Effects and Adverse Reactions; Electrocardiography; European Continental Ancestry Group; Gene-Environment Interaction; Genome-Wide Association Study; Humans; Linear Models; Long QT Syndrome; Markov Chains; Pharmacogenetics; Polymorphism, Single Nucleotide; Quantitative Trait, Heritable

Effect of genetic variants associated with plasma homocysteine levels on stroke risk. - Cotlarciuc, Ioana; Malik, Rainer; Holliday, Elizabeth G; Ahmadi, Kourosh R; Paré, Guillaume; Psaty, Bruce M; Fornage, Myriam; Hasan, Nazeeha; Rinne, Paul E; Ikram, M Arfan; Markus, Hugh S; Rosand, Jonathan; et al. (Stroke, 2014)
BACKGROUND AND PURPOSE: Elevated total plasma homocysteine (tHcy) levels are known to be associated with increased risk of ischemic stroke (IS). Given that both tHcy and IS are heritable traits, we investigated a potential genetic relationship between homocysteine levels and stroke risk by assessing 18 polymorphisms previously associated with tHcy levels for their association with IS and its subtypes. METHODS: Previous meta-analysis results from an international stroke collaborative network, METASTROKE, were used to assess association of the 18 tHcy-associated single-nucleotide polymorphisms (SNPs) in 12 389 IS cases and 62 004 controls. We also investigated the associations in regions located within 50 kb from the 18 tHcy-related SNPs and the association of a genetic risk score, including the 18 SNPs. RESULTS: One SNP located in the RASIP1 gene and a cluster of 3 SNPs located at and near SLC17A3 were significantly associated with IS (P<0.0003) after correcting for multiple testing. For stroke subtypes, the sentinel SNP located upstream of MUT was significantly associated with small-vessel disease (P=0.0022), whereas 1 SNP located in MTHFR was significantly associated with large-vessel disease (P=0.00019). A genetic risk score, including the 18 SNPs, did not show significant association with IS or its subtypes. CONCLUSIONS: This study found several potential associations with IS and its subtypes: an association of an MUT variant with small-vessel disease, an MTHFR variant with large-vessel disease, and associations of RASIP1 and SLC17A3 variants with overall IS.
Keywords: Brain Ischemia; Cohort Studies; Europe; Genetic Association Studies; Genetic Loci; Genetic Predisposition to Disease; Genetic Variation; Genome; Homocysteine; Humans; Polymorphism, Single Nucleotide; Risk; Stroke

Effects of long-term averaging of quantitative blood pressure traits on the detection of genetic associations. - Ganesh, Santhi K; Chasman, Daniel I; Larson, Martin G; Guo, Xiuqing; Verwoert, Germain; Bis, Joshua C; Gu, Xiangjun; Smith, Albert V; Yang, Min-Lee; Zhang, Yan; Ehret, Georg; Rose, Lynda M; et al. (Am J Hum Genet, 2014)
Blood pressure (BP) is a heritable, quantitative trait with intraindividual variability and susceptibility to measurement error. Genetic studies of BP generally use single-visit measurements and thus cannot remove variability occurring over months or years. We leveraged the idea that averaging BP measured across time would improve phenotypic accuracy and thereby increase statistical power to detect genetic associations. We studied systolic BP (SBP), diastolic BP (DBP), mean arterial pressure (MAP), and pulse pressure (PP) averaged over multiple years in 46,629 individuals of European ancestry. We identified 39 trait-variant associations across 19 independent loci (p < 5 × 10(-8)); five associations (in four loci) uniquely identified by our LTA analyses included those of SBP and MAP at 2p23 (rs1275988, near KCNK3), DBP at 2q11.2 (rs7599598, in FER1L5), and PP at 6p21 (rs10948071, near CRIP3) and 7p13 (rs2949837, near IGFBP3). Replication analyses conducted in cohorts with single-visit BP data showed positive replication of associations and a nominal association (p < 0.05). We estimated a 20% gain in statistical power with long-term average (LTA) as compared to single-visit BP association studies. Using LTA analysis, we identified genetic loci influencing BP. LTA might be one way of increasing the power of genetic associations for continuous traits in extant samples for other phenotypes that are measured serially over time.
Keywords: Blood Pressure; Genome-Wide Association Study; Humans; Longitudinal Studies; Phenotype; Polymorphism, Single Nucleotide; Quantitative Trait Loci

Estimated GFR and circulating 24,25-dihydroxyvitamin D3 concentration: a participant-level analysis of 5 cohort studies and clinical trials. - de Boer, Ian H; Sachs, Michael C; Chonchol, Michel; Himmelfarb, Jonathan; Hoofnagle, Andrew N; Ix, Joachim H; Kremsdorf, Robin A; Lin, Yvonne S; Mehrotra, Rajnish; Robinson-Cohen, Cassianne; Siscovick, David S; Steffes, Michael W; et al. (Am J Kidney Dis, 2014)
BACKGROUND: Decreased glomerular filtration rate (GFR) leads to reduced production of 1,25-dihydroxyvitamin D3 from 25-hydroxyvitamin D3 (25[OH]D3). Effects of low GFR on vitamin D catabolism are less well understood. We tested associations of estimated GFR (eGFR) with the circulating concentration of 24,25-dihydroxyvitamin D3 (24,25[OH]2D3), the most abundant product of 25(OH)D3 catabolism, across populations with a wide range of GFRs. STUDY DESIGN: Cross-sectional study. SETTING & PARTICIPANTS: 9,596 participants in 5 cohort studies and clinical trials: the Diabetes Control and Complications Trial (N=1,193), Multi-Ethnic Study of Atherosclerosis (N=6,470), Cardiovascular Health Study (N=932), Seattle Kidney Study (N=289), and Hemodialysis Study (N=712). PREDICTOR: eGFR. OUTCOME: Circulating 24,25(OH)2D3 concentration. MEASUREMENTS: GFR was estimated from serum creatinine using the Chronic Kidney Disease Epidemiology Collaboration equation. Vitamin D metabolites were measured by mass spectrometry. RESULTS: Circulating 24,25(OH)2D3 concentration was correlated with circulating 25(OH)D3 concentration (Pearson r range, 0.64-0.88). This correlation was weaker with lower eGFRs. Moreover, the increment in 24,25(OH)2D3 concentration associated with higher 25(OH)D3 concentration (slope) was lower with lower eGFRs: 2.06 (95% CI, 2.01-2.10), 1.77 (95% CI, 1.74-1.81), 1.55 (95% CI, 1.48-1.62), 1.17 (95% CI, 1.05-1.29), 0.92 (95% CI, 0.74-1.10), 0.61 (95% CI, 0.22-1.00), and 0.37 (95% CI, 0.35-0.39) ng/mL of 24,25(OH)2D3 per 10 ng/mL of 25(OH)D3 for eGFRs≥90, 60-89, 45-59, 30-44, 15-29, and <15 mL/min/1.73 m2 and end-stage renal disease treated with hemodialysis, respectively. As a result, at a 25(OH)D3 concentration of 20 ng/mL, mean 24,25(OH)2D3 concentrations were 2.92 (95% CI, 2.87-2.96), 2.68 (95% CI, 2.64-2.72), 2.35 (95% CI, 2.26-2.45), 1.92 (95% CI, 1.74-2.10), 1.69 (95% CI, 1.43-1.95), 1.14 (95% CI, 0.62-1.66), and 1.04 (95% CI,1.02-1.07) ng/mL for each category, respectively. This interaction was independent of other relevant clinical characteristics. Race, diabetes, urine albumin excretion, and circulating parathyroid hormone and fibroblast growth factor 23 concentrations more modestly modified the association of 24,25(OH)2D3 with 25(OH)D3. LIMITATIONS: Lack of direct pharmacokinetic measurements of vitamin D catabolism. CONCLUSIONS: Lower eGFR is associated strongly with reduced vitamin D catabolism, as measured by circulating 24,25(OH)2D3 concentration.
Keywords: 24,25-Dihydroxyvitamin D 3; Adult; Aged; Aged, 80 and over; Biomarkers; Cohort Studies; Cross-Sectional Studies; Diabetes Mellitus; Female; Glomerular Filtration Rate; Humans; Kidney Failure, Chronic; Male; Middle Aged; Observational Studies as Topic; Randomized Controlled Trials as Topic; Young Adult

Evidence of heterogeneity by race/ethnicity in genetic determinants of QT interval. - Seyerle, Amanda A; Young, Alicia M; Jeff, Janina M; Melton, Phillip E; Jorgensen, Neal W; Lin, Yi; Carty, Cara L; Deelman, Ewa; Heckbert, Susan R; Hindorff, Lucia A; Jackson, Rebecca D; Martin, Lisa W; et al. (Epidemiology, 2014)
BACKGROUND: QT interval (QT) prolongation is an established risk factor for ventricular tachyarrhythmia and sudden cardiac death. Previous genome-wide association studies in populations of the European descent have identified multiple genetic loci that influence QT, but few have examined these loci in ethnically diverse populations. METHODS: Here, we examine the direction, magnitude, and precision of effect sizes for 21 previously reported SNPs from 12 QT loci, in populations of European (n = 16,398), African (n = 5,437), American Indian (n = 5,032), Hispanic (n = 1,143), and Asian (n = 932) descent as part of the Population Architecture using Genomics and Epidemiology (PAGE) study. Estimates obtained from linear regression models stratified by race/ethnicity were combined using inverse-variance weighted meta-analysis. Heterogeneity was evaluated using Cochran's Q test. RESULTS: Of 21 SNPs, 7 showed consistent direction of effect across all 5 populations, and an additional 9 had estimated effects that were consistent across 4 populations. Despite consistent direction of effect, 9 of 16 SNPs had evidence (P < 0.05) of heterogeneity by race/ethnicity. For these 9 SNPs, linkage disequilibrium plots often indicated substantial variation in linkage disequilibrium patterns among the various racial/ethnic groups, as well as possible allelic heterogeneity. CONCLUSIONS: These results emphasize the importance of analyzing racial/ethnic groups separately in genetic studies. Furthermore, they underscore the possible utility of trans-ethnic studies to pinpoint underlying casual variants influencing heritable traits such as QT.
Keywords: Aged; Continental Population Groups; Electrocardiography; Female; Genetic Predisposition to Disease; Haplotypes; Humans; Long QT Syndrome; Male; Middle Aged; Phenotype; Polymorphism, Single Nucleotide; Quantitative Trait Loci; Quantitative Trait, Heritable; Risk Factors

FTO genetic variants, dietary intake and body mass index: insights from 177,330 individuals. - Qi, Qibin; Kilpeläinen, Tuomas O; Downer, Mary K; Tanaka, Toshiko; Smith, Caren E; Sluijs, Ivonne; Sonestedt, Emily; Chu, Audrey Y; Renstrom, Frida; Lin, Xiaochen; Ängquist, Lars H; Huang, Jinyan; et al. (Hum Mol Genet, 2014)
FTO is the strongest known genetic susceptibility locus for obesity. Experimental studies in animals suggest the potential roles of FTO in regulating food intake. The interactive relation among FTO variants, dietary intake and body mass index (BMI) is complex and results from previous often small-scale studies in humans are highly inconsistent. We performed large-scale analyses based on data from 177,330 adults (154 439 Whites, 5776 African Americans and 17 115 Asians) from 40 studies to examine: (i) the association between the FTO-rs9939609 variant (or a proxy single-nucleotide polymorphism) and total energy and macronutrient intake and (ii) the interaction between the FTO variant and dietary intake on BMI. The minor allele (A-allele) of the FTO-rs9939609 variant was associated with higher BMI in Whites (effect per allele = 0.34 [0.31, 0.37] kg/m(2), P = 1.9 × 10(-105)), and all participants (0.30 [0.30, 0.35] kg/m(2), P = 3.6 × 10(-107)). The BMI-increasing allele of the FTO variant showed a significant association with higher dietary protein intake (effect per allele = 0.08 [0.06, 0.10] %, P = 2.4 × 10(-16)), and relative weak associations with lower total energy intake (-6.4 [-10.1, -2.6] kcal/day, P = 0.001) and lower dietary carbohydrate intake (-0.07 [-0.11, -0.02] %, P = 0.004). The associations with protein (P = 7.5 × 10(-9)) and total energy (P = 0.002) were attenuated but remained significant after adjustment for BMI. We did not find significant interactions between the FTO variant and dietary intake of total energy, protein, carbohydrate or fat on BMI. Our findings suggest a positive association between the BMI-increasing allele of FTO variant and higher dietary protein intake and offer insight into potential link between FTO, dietary protein intake and adiposity.
Keywords: Adult; African Americans; Aged; Alleles; Asian Continental Ancestry Group; Body Mass Index; Dietary Carbohydrates; Dietary Fats; Dietary Proteins; Energy Intake; European Continental Ancestry Group; Female; Gene Frequency; Humans; Male; Middle Aged; Obesity; Polymorphism, Single Nucleotide; Proteins

Gender and telomere length: systematic review and meta-analysis. - Gardner, Michael; Bann, David; Wiley, Laura; Cooper, Rachel; Hardy, Rebecca; Nitsch, Dorothea; Martin-Ruiz, Carmen; Shiels, Paul; Sayer, Avan Aihie; Barbieri, Michelangela; Bekaert, Sofie; Bischoff, Claus; et al. (Exp Gerontol, 2014)
BACKGROUND: It is widely believed that females have longer telomeres than males, although results from studies have been contradictory. METHODS: We carried out a systematic review and meta-analyses to test the hypothesis that in humans, females have longer telomeres than males and that this association becomes stronger with increasing age. Searches were conducted in EMBASE and MEDLINE (by November 2009) and additional datasets were obtained from study investigators. Eligible observational studies measured telomeres for both females and males of any age, had a minimum sample size of 100 and included participants not part of a diseased group. We calculated summary estimates using random-effects meta-analyses. Heterogeneity between studies was investigated using sub-group analysis and meta-regression. RESULTS: Meta-analyses from 36 cohorts (36,230 participants) showed that on average females had longer telomeres than males (standardised difference in telomere length between females and males 0.090, 95% CI 0.015, 0.166; age-adjusted). There was little evidence that these associations varied by age group (p=1.00) or cell type (p=0.29). However, the size of this difference did vary by measurement methods, with only Southern blot but neither real-time PCR nor Flow-FISH showing a significant difference. This difference was not associated with random measurement error. CONCLUSIONS: Telomere length is longer in females than males, although this difference was not universally found in studies that did not use Southern blot methods. Further research on explanations for the methodological differences is required.
Keywords: Adult; Aged; Aged, 80 and over; Aging; Female; Humans; Male; Middle Aged; Sex Factors; Telomere

Gene-age interactions in blood pressure regulation: a large-scale investigation with the CHARGE, Global BPgen, and ICBP Consortia. - Simino, Jeannette; Shi, Gang; Bis, Joshua C; Chasman, Daniel I; Ehret, Georg B; Gu, Xiangjun; Guo, Xiuqing; Hwang, Shih-Jen; Sijbrands, Eric; Smith, Albert V; Verwoert, Germaine C; Bragg-Gresham, Jennifer L; et al. (Am J Hum Genet, 2014)
Although age-dependent effects on blood pressure (BP) have been reported, they have not been systematically investigated in large-scale genome-wide association studies (GWASs). We leveraged the infrastructure of three well-established consortia (CHARGE, GBPgen, and ICBP) and a nonstandard approach (age stratification and metaregression) to conduct a genome-wide search of common variants with age-dependent effects on systolic (SBP), diastolic (DBP), mean arterial (MAP), and pulse (PP) pressure. In a two-staged design using 99,241 individuals of European ancestry, we identified 20 genome-wide significant (p ≤ 5 × 10(-8)) loci by using joint tests of the SNP main effect and SNP-age interaction. Nine of the significant loci demonstrated nominal evidence of age-dependent effects on BP by tests of the interactions alone. Index SNPs in the EHBP1L1 (DBP and MAP), CASZ1 (SBP and MAP), and GOSR2 (PP) loci exhibited the largest age interactions, with opposite directions of effect in the young versus the old. The changes in the genetic effects over time were small but nonnegligible (up to 1.58 mm Hg over 60 years). The EHBP1L1 locus was discovered through gene-age interactions only in whites but had DBP main effects replicated (p = 8.3 × 10(-4)) in 8,682 Asians from Singapore, indicating potential interethnic heterogeneity. A secondary analysis revealed 22 loci with evidence of age-specific effects (e.g., only in 20 to 29-year-olds). Age can be used to select samples with larger genetic effect sizes and more homogenous phenotypes, which may increase statistical power. Age-dependent effects identified through novel statistical approaches can provide insight into the biology and temporal regulation underlying BP associations.
Keywords: Adolescent; Adult; Age Factors; Aged; Blood Pressure; Cohort Studies; Humans; Middle Aged; Young Adult

Gene-centric meta-analyses for central adiposity traits in up to 57 412 individuals of European descent confirm known loci and reveal several novel associations. - Yoneyama, Sachiko; Guo, Yiran; Lanktree, Matthew B; Barnes, Michael R; Elbers, Clara C; Karczewski, Konrad J; Padmanabhan, Sandosh; Bauer, Florianne; Baumert, Jens; Beitelshees, Amber; Berenson, Gerald S; Boer, Jolanda M A; et al. (Hum Mol Genet, 2014)
Waist circumference (WC) and waist-to-hip ratio (WHR) are surrogate measures of central adiposity that are associated with adverse cardiovascular events, type 2 diabetes and cancer independent of body mass index (BMI). WC and WHR are highly heritable with multiple susceptibility loci identified to date. We assessed the association between SNPs and BMI-adjusted WC and WHR and unadjusted WC in up to 57 412 individuals of European descent from 22 cohorts collaborating with the NHLBI's Candidate Gene Association Resource (CARe) project. The study population consisted of women and men aged 20-80 years. Study participants were genotyped using the ITMAT/Broad/CARE array, which includes ∼50 000 cosmopolitan tagged SNPs across ∼2100 cardiovascular-related genes. Each trait was modeled as a function of age, study site and principal components to control for population stratification, and we conducted a fixed-effects meta-analysis. No new loci for WC were observed. For WHR analyses, three novel loci were significantly associated (P < 2.4 × 10(-6)). Previously unreported rs2811337-G near TMCC1 was associated with increased WHR (β ± SE, 0.048 ± 0.008, P = 7.7 × 10(-9)) as was rs7302703-G in HOXC10 (β = 0.044 ± 0.008, P = 2.9 × 10(-7)) and rs936108-C in PEMT (β = 0.035 ± 0.007, P = 1.9 × 10(-6)). Sex-stratified analyses revealed two additional novel signals among females only, rs12076073-A in SHC1 (β = 0.10 ± 0.02, P = 1.9 × 10(-6)) and rs1037575-A in ATBDB4 (β = 0.046 ± 0.01, P = 2.2 × 10(-6)), supporting an already established sexual dimorphism of central adiposity-related genetic variants. Functional analysis using ENCODE and eQTL databases revealed that several of these loci are in regulatory regions or regions with differential expression in adipose tissue.
Keywords: Adiposity; Adult; Aged; Aged, 80 and over; Body Mass Index; European Continental Ancestry Group; Female; Genome-Wide Association Study; Humans; Male; Middle Aged; Waist Circumference; Waist-Hip Ratio; Young Adult

A genetic association study of D-dimer levels with 50K SNPs from a candidate gene chip in four ethnic groups. - Weng, Lu-Chen; Tang, Weihong; Rich, Stephen S; Smith, Nicholas L; Redline, Susan; O'Donnell, Christopher J; Basu, Saonli; Reiner, Alexander P; Delaney, Joseph A; Tracy, Russell P; Palmer, Cameron D; Young, Taylor; et al. (Thromb Res, 2014)
INTRODUCTION: D-dimer, a fibrin degradation product, is related to risk of cardiovascular disease and venous thromboembolism. Genetic determinants of D-dimer are not well characterized; notably, few data have been reported for African American (AA), Asian, and Hispanic populations. MATERIALS AND METHODS: We conducted a large-scale candidate gene association study to identify variants in genes associated with D-dimer levels in multi-ethnic populations. Four cohorts, comprising 6,848 European Americans (EAs), 2,192 AAs, 670 Asians, and 1,286 Hispanics in the National Heart, Lung, and Blood Institute Candidate Gene Association Resource consortium, were assembled. Approximately 50,000 genotyped single nucleotide polymorphisms (SNPs) in 2,000 cardiovascular disease gene loci were analyzed by linear regression, adjusting for age, sex, study site, and principal components in each cohort and ethnic group. Results across studies were combined within each ethnic group by meta-analysis. RESULTS: Twelve SNPs in coagulation factor V (F5) and 3 SNPs in the fibrinogen alpha chain (FGA) were significantly associated with D-dimer level in EAs with p<2.0×10(-6). The signal for the most associated SNP in F5 (rs6025, factor V Leiden) was replicated in Hispanics (p=0.023), while that for the top functional SNP in FGA (rs6050) was replicated in AAs (p=0.006). No additional SNPs were significantly associated with D-dimer. CONCLUSIONS: Our study replicated previously reported associations of D-dimer with SNPs in F5 and FGA in EAs; we demonstrated replication of the association of D-dimer with FGA rs6050 in AAs and the factor V Leiden variant in Hispanics.
Keywords: Adult; Aged; Cardiovascular Diseases; Ethnic Groups; Factor V; Female; Fibrin Fibrinogen Degradation Products; Fibrinogen; Genetic Association Studies; Genotype; Humans; Male; Middle Aged; Oligonucleotide Array Sequence Analysis; Polymorphism, Single Nucleotide; Young Adult

Genetic association study of QT interval highlights role for calcium signaling pathways in myocardial repolarization. - Arking, Dan E; Pulit, Sara L; Crotti, Lia; van der Harst, Pim; Munroe, Patricia B; Koopmann, Tamara T; Sotoodehnia, Nona; Rossin, Elizabeth J; Morley, Michael; Wang, Xinchen; Johnson, Andrew D; Lundby, Alicia; et al. (Nat Genet, 2014)
The QT interval, an electrocardiographic measure reflecting myocardial repolarization, is a heritable trait. QT prolongation is a risk factor for ventricular arrhythmias and sudden cardiac death (SCD) and could indicate the presence of the potentially lethal mendelian long-QT syndrome (LQTS). Using a genome-wide association and replication study in up to 100,000 individuals, we identified 35 common variant loci associated with QT interval that collectively explain ∼8-10% of QT-interval variation and highlight the importance of calcium regulation in myocardial repolarization. Rare variant analysis of 6 new QT interval-associated loci in 298 unrelated probands with LQTS identified coding variants not found in controls but of uncertain causality and therefore requiring validation. Several newly identified loci encode proteins that physically interact with other recognized repolarization proteins. Our integration of common variant association, expression and orthogonal protein-protein interaction screens provides new insights into cardiac electrophysiology and identifies new candidate genes for ventricular arrhythmias, LQTS and SCD.
Keywords: Adult; Aged; Arrhythmias, Cardiac; Calcium Signaling; Death, Sudden, Cardiac; Electrocardiography; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Genotype; Heart Ventricles; Humans; Long QT Syndrome; Male; Middle Aged; Myocardium; Polymorphism, Single Nucleotide

Genetic determinants of age-related macular degeneration in diverse populations from the PAGE study. - Restrepo, Nicole A; Spencer, Kylee L; Goodloe, Robert; Garrett, Tiana A; Heiss, Gerardo; Bůzková, Petra; Jorgensen, Neal; Jensen, Richard A; Matise, Tara C; Hindorff, Lucia A; Klein, Barbara E K; Klein, Ronald; et al. (Invest Ophthalmol Vis Sci, 2014)
PURPOSE: Substantial progress has been made in identifying susceptibility variants for AMD in European populations; however, few studies have been conducted to understand the role these variants play in AMD risk in diverse populations. The present study aims to examine AMD risk across diverse populations in known and suspected AMD complement factor and lipid-related loci. METHODS: Targeted genotyping was performed across study sites for AMD and lipid trait-associated single nucleotide polymorphism (SNPs). Genetic association tests were performed at individual sites and then meta-analyzed using logistic regression assuming an additive genetic model stratified by self-described race/ethnicity. Participants included cases with early or late AMD and controls with no signs of AMD as determined by fundus photography. Populations included in this study were European Americans, African Americans, Mexican Americans, and Singaporeans from the Population Architecture using Genomics and Epidemiology (PAGE) study. RESULTS: Index variants of AMD, rs1061170 (CFH) and rs10490924 (ARMS2), were associated with AMD at P=3.05×10(-8) and P=6.36×10(-6), respectively, in European Americans. In general, none of the major AMD index variants generalized to our non-European populations with the exception of rs10490924 in Mexican Americans at an uncorrected P value<0.05. Four lipid-associated SNPS (LPL rs328, TRIB1 rs6987702, CETP rs1800775, and KCTD10/MVK rs2338104) were associated with AMD in African Americans and Mexican Americans (P<0.05), but these associations did not survive strict corrections for multiple testing. CONCLUSIONS: While most associations did not generalize in the non-European populations, variants within lipid-related genes were found to be associated with AMD. This study highlights the need for larger well-powered studies in non-European populations.
Keywords: Adult; Aged; Aged, 80 and over; Complement Factor H; DNA; Ethnic Groups; Female; Gene Frequency; Genetic Predisposition to Disease; Genotype; Humans; Macular Degeneration; Male; Middle Aged; Phenotype; Polymorphism, Single Nucleotide; Prevalence; Prospective Studies; Proteins; Risk Factors; United States

Genetic diversity is a predictor of mortality in humans. - Bihlmeyer, Nathan A; Brody, Jennifer A; Smith, Albert Vernon; Lunetta, Kathryn L; Nalls, Mike; Smith, Jennifer A; Tanaka, Toshiko; Davies, Gail; Yu, Lei; Mirza, Saira Saeed; Teumer, Alexander; Coresh, Josef; et al. (BMC Genet, 2014)
BACKGROUND: It has been well-established, both by population genetics theory and direct observation in many organisms, that increased genetic diversity provides a survival advantage. However, given the limitations of both sample size and genome-wide metrics, this hypothesis has not been comprehensively tested in human populations. Moreover, the presence of numerous segregating small effect alleles that influence traits that directly impact health directly raises the question as to whether global measures of genomic variation are themselves associated with human health and disease. RESULTS: We performed a meta-analysis of 17 cohorts followed prospectively, with a combined sample size of 46,716 individuals, including a total of 15,234 deaths. We find a significant association between increased heterozygosity and survival (P = 0.03). We estimate that within a single population, every standard deviation of heterozygosity an individual has over the mean decreases that person's risk of death by 1.57%. CONCLUSIONS: This effect was consistent between European and African ancestry cohorts, men and women, and major causes of death (cancer and cardiovascular disease), demonstrating the broad positive impact of genomic diversity on human survival.
Keywords: Genome-Wide Association Study; Heterozygote; Humans; Mortality; Polymorphism, Single Nucleotide; Proportional Hazards Models

Gene-wide analysis detects two new susceptibility genes for Alzheimer's disease. - Escott-Price, Valentina; Bellenguez, Céline; Wang, Li-San; Choi, Seung-Hoan; Harold, Denise; Jones, Lesley; Holmans, Peter; Gerrish, Amy; Vedernikov, Alexey; Richards, Alexander; DeStefano, Anita L; Lambert, Jean-Charles; et al. (PLoS One, 2014)
BACKGROUND: Alzheimer's disease is a common debilitating dementia with known heritability, for which 20 late onset susceptibility loci have been identified, but more remain to be discovered. This study sought to identify new susceptibility genes, using an alternative gene-wide analytical approach which tests for patterns of association within genes, in the powerful genome-wide association dataset of the International Genomics of Alzheimer's Project Consortium, comprising over 7 m genotypes from 25,580 Alzheimer's cases and 48,466 controls. PRINCIPAL FINDINGS: In addition to earlier reported genes, we detected genome-wide significant loci on chromosomes 8 (TP53INP1, p = 1.4×10-6) and 14 (IGHV1-67 p = 7.9×10-8) which indexed novel susceptibility loci. SIGNIFICANCE: The additional genes identified in this study, have an array of functions previously implicated in Alzheimer's disease, including aspects of energy metabolism, protein degradation and the immune system and add further weight to these pathways as potential therapeutic targets in Alzheimer's disease.
Keywords: Alzheimer Disease; Carrier Proteins; Case-Control Studies; Genome-Wide Association Study; Heat-Shock Proteins; Humans; Polymorphism, Single Nucleotide; Receptors, Antigen, B-Cell

Genome-wide association analysis identifies six new loci associated with forced vital capacity. - Loth, Daan W; Soler Artigas, Maria; Gharib, Sina A; Wain, Louise V; Franceschini, Nora; Koch, Beate; Pottinger, Tess D; Smith, Albert Vernon; Duan, Qing; Oldmeadow, Chris; Lee, Mi Kyeong; Strachan, David P; et al. (Nat Genet, 2014)
Forced vital capacity (FVC), a spirometric measure of pulmonary function, reflects lung volume and is used to diagnose and monitor lung diseases. We performed genome-wide association study meta-analysis of FVC in 52,253 individuals from 26 studies and followed up the top associations in 32,917 additional individuals of European ancestry. We found six new regions associated at genome-wide significance (P < 5 × 10(-8)) with FVC in or near EFEMP1, BMP6, MIR129-2-HSD17B12, PRDM11, WWOX and KCNJ2. Two loci previously associated with spirometric measures (GSTCD and PTCH1) were related to FVC. Newly implicated regions were followed up in samples from African-American, Korean, Chinese and Hispanic individuals. We detected transcripts for all six newly implicated genes in human lung tissue. The new loci may inform mechanisms involved in lung development and the pathogenesis of restrictive lung disease.
Keywords: Cohort Studies; Databases, Genetic; Follow-Up Studies; Forced Expiratory Volume; Genetic Loci; Genetic Predisposition to Disease; Genome, Human; Genome-Wide Association Study; Humans; Lung Diseases; Meta-Analysis as Topic; Polymorphism, Single Nucleotide; Prognosis; Quantitative Trait Loci; Respiratory Function Tests; Spirometry; Vital Capacity

Genome-wide association study for circulating tissue plasminogen activator levels and functional follow-up implicates endothelial STXBP5 and STX2. - Huang, Jie; Huffman, Jennifer E; Yamakuchi, Munekazu; Yamkauchi, Munekazu; Trompet, Stella; Asselbergs, Folkert W; Sabater-Lleal, Maria; Trégouët, David-Alexandre; Chen, Wei-Min; Smith, Nicholas L; Kleber, Marcus E; Shin, So-Youn; et al. (Arterioscler Thromb Vasc Biol, 2014)
OBJECTIVE: Tissue plasminogen activator (tPA), a serine protease, catalyzes the conversion of plasminogen to plasmin, the major enzyme responsible for endogenous fibrinolysis. In some populations, elevated plasma levels of tPA have been associated with myocardial infarction and other cardiovascular diseases. We conducted a meta-analysis of genome-wide association studies to identify novel correlates of circulating levels of tPA. APPROACH AND RESULTS: Fourteen cohort studies with tPA measures (N=26 929) contributed to the meta-analysis. Three loci were significantly associated with circulating tPA levels (P<5.0×10(-8)). The first locus is on 6q24.3, with the lead single nucleotide polymorphism (SNP; rs9399599; P=2.9×10(-14)) within STXBP5. The second locus is on 8p11.21. The lead SNP (rs3136739; P=1.3×10(-9)) is intronic to POLB and <200 kb away from the tPA encoding the gene PLAT. We identified a nonsynonymous SNP (rs2020921) in modest linkage disequilibrium with rs3136739 (r(2)=0.50) within exon 5 of PLAT (P=2.0×10(-8)). The third locus is on 12q24.33, with the lead SNP (rs7301826; P=1.0×10(-9)) within intron 7 of STX2. We further found evidence for the association of lead SNPs in STXBP5 and STX2 with expression levels of the respective transcripts. In in vitro cell studies, silencing STXBP5 decreased the release of tPA from vascular endothelial cells, whereas silencing STX2 increased the tPA release. Through an in silico lookup, we found no associations of the 3 lead SNPs with coronary artery disease or stroke. CONCLUSIONS: We identified 3 loci associated with circulating tPA levels, the PLAT region, STXBP5, and STX2. Our functional studies implicate a novel role for STXBP5 and STX2 in regulating tPA release.
Keywords: Aged; Cells, Cultured; Coronary Artery Disease; Endothelial Cells; Europe; Female; Gene Expression Regulation; Gene Silencing; Genetic Loci; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Male; Middle Aged; Nerve Tissue Proteins; Phenotype; Polymorphism, Single Nucleotide; R-SNARE Proteins; Risk Factors; Stroke; Syntaxin 1; Tissue Plasminogen Activator; Transfection; United States; Up-Regulation

Genome-wide association study of L-arginine and dimethylarginines reveals novel metabolic pathway for symmetric dimethylarginine. - Lüneburg, Nicole; Lieb, Wolfgang; Zeller, Tanja; Chen, Ming-Huei; Maas, Renke; Carter, Angela M; Xanthakis, Vanessa; Glazer, Nicole L; Schwedhelm, Edzard; Seshadri, Sudha; Ikram, Mohammad Arfan; Longstreth, William T; et al. (Circ Cardiovasc Genet, 2014)
BACKGROUND: Dimethylarginines (DMA) interfere with nitric oxide formation by inhibiting nitric oxide synthase (asymmetrical DMA [ADMA]) and l-arginine uptake into the cell (ADMA and symmetrical DMA [SDMA]). In prospective clinical studies, ADMA has been characterized as a cardiovascular risk marker, whereas SDMA is a novel marker for renal function and associated with all-cause mortality after ischemic stroke. The aim of the current study was to characterize the environmental and genetic contributions to interindividual variability of these biomarkers. METHODS AND RESULTS: This study comprised a genome-wide association analysis of 3 well-characterized population-based cohorts (Framingham Heart Study [FHS; n=2992], Gutenberg Health Study [GHS; n=4354], and Multinational Monitoring of Trends and Determinants in Cardiovascular Disease Study [MONICA]/Cooperative Health Research in the Augsburg Area, Augsburg, Bavaria, Germany [KORA] F3 [n=581]) and identified replicated loci (DDAH1, MED23, Arg1, and AGXT2) associated with the interindividual variability in ADMA, l-arginine, and SDMA. Experimental in silico and in vitro studies confirmed functional significance of the identified AGXT2 variants. Clinical outcome analysis in 384 patients of the Leeds stroke study demonstrated an association between increased plasma levels of SDMA, AGXT2 variants, and various cardiometabolic risk factors. AGXT2 variants were not associated with poststroke survival in the Leeds study or were they associated with incident stroke in the Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) consortium. CONCLUSIONS: These genome-wide association study support the importance of DDAH1 and MED23/Arg1 in regulating ADMA and l-arginine metabolism, respectively, and identify a novel regulatory renal pathway for SDMA by AGXT2. AGXT2 variants might explain part of the pathogenic link between SDMA, renal function, and outcome. An association between AGXT2 variants and stroke is unclear and warrants further investigation.
Keywords: Adult; Aged; Amidohydrolases; Arginine; Binding Sites; Cohort Studies; Female; Genetic Loci; Genome-Wide Association Study; Genotype; HEK293 Cells; Humans; Male; Mediator Complex; Middle Aged; Polymorphism, Single Nucleotide; Protein Structure, Tertiary; Risk Factors; Stroke; Substrate Specificity; Transaminases

Genome-wide association study of plasma N6 polyunsaturated fatty acids within the cohorts for heart and aging research in genomic epidemiology consortium. - Guan, Weihua; Steffen, Brian T; Lemaitre, Rozenn N; Wu, Jason H Y; Tanaka, Toshiko; Manichaikul, Ani; Foy, Millennia; Rich, Stephen S; Wang, Lu; Nettleton, Jennifer A; Tang, Weihong; Gu, Xiangjun; et al. (Circ Cardiovasc Genet, 2014)
BACKGROUND: Omega6 (n6) polyunsaturated fatty acids (PUFAs) and their metabolites are involved in cell signaling, inflammation, clot formation, and other crucial biological processes. Genetic components, such as variants of fatty acid desaturase (FADS) genes, determine the composition of n6 PUFAs. METHODS AND RESULTS: To elucidate undiscovered biological pathways that may influence n6 PUFA composition, we conducted genome-wide association studies and meta-analyses of associations of common genetic variants with 6 plasma n6 PUFAs in 8631 white adults (55% women) across 5 prospective studies. Plasma phospholipid or total plasma fatty acids were analyzed by similar gas chromatography techniques. The n6 fatty acids linoleic acid (LA), γ-linolenic acid (GLA), dihomo-GLA, arachidonic acid, and adrenic acid were expressed as percentage of total fatty acids. We performed linear regression with robust SEs to test for single-nucleotide polymorphism-fatty acid associations, with pooling using inverse-variance-weighted meta-analysis. Novel regions were identified on chromosome 10 associated with LA (rs10740118; P=8.1×10(-9); near NRBF2), on chromosome 16 with LA, GLA, dihomo-GLA, and arachidonic acid (rs16966952; P=1.2×10(-15), 5.0×10(-11), 7.6×10(-65), and 2.4×10(-10), respectively; NTAN1), and on chromosome 6 with adrenic acid after adjustment for arachidonic acid (rs3134950; P=2.1×10(-10); AGPAT1). We confirmed previous findings of the FADS cluster on chromosome 11 with LA and arachidonic acid, and further observed novel genome-wide significant association of this cluster with GLA, dihomo-GLA, and adrenic acid (P=2.3×10(-72), 2.6×10(-151), and 6.3×10(-140), respectively). CONCLUSIONS: Our findings suggest that along with the FADS gene cluster, additional genes may influence n6 PUFA composition.
Keywords: Adult; Aged; Aged, 80 and over; Aging; Chromosomes, Human, Pair 10; Chromosomes, Human, Pair 16; Chromosomes, Human, Pair 6; Fatty Acid Desaturases; Fatty Acids, Omega-6; Female; Genome-Wide Association Study; Genomics; Heart Diseases; Humans; Male; Middle Aged; Polymorphism, Single Nucleotide; Prospective Studies; Sequence Analysis, DNA

Glycated hemoglobin measurement and prediction of cardiovascular disease. - Di Angelantonio, Emanuele; Gao, Pei; Khan, Hassan; Butterworth, Adam S; Wormser, David; Kaptoge, Stephen; Kondapally Seshasai, Sreenivasa Rao; Thompson, Alex; Sarwar, Nadeem; Willeit, Peter; Ridker, Paul M; Barr, Elizabeth L M; et al. (JAMA, 2014)
IMPORTANCE: The value of measuring levels of glycated hemoglobin (HbA1c) for the prediction of first cardiovascular events is uncertain. OBJECTIVE: To determine whether adding information on HbA1c values to conventional cardiovascular risk factors is associated with improvement in prediction of cardiovascular disease (CVD) risk. DESIGN, SETTING, AND PARTICIPANTS: Analysis of individual-participant data available from 73 prospective studies involving 294,998 participants without a known history of diabetes mellitus or CVD at the baseline assessment. MAIN OUTCOMES AND MEASURES: Measures of risk discrimination for CVD outcomes (eg, C-index) and reclassification (eg, net reclassification improvement) of participants across predicted 10-year risk categories of low (<5%), intermediate (5% to <7.5%), and high (≥ 7.5%) risk. RESULTS: During a median follow-up of 9.9 (interquartile range, 7.6-13.2) years, 20,840 incident fatal and nonfatal CVD outcomes (13,237 coronary heart disease and 7603 stroke outcomes) were recorded. In analyses adjusted for several conventional cardiovascular risk factors, there was an approximately J-shaped association between HbA1c values and CVD risk. The association between HbA1c values and CVD risk changed only slightly after adjustment for total cholesterol and triglyceride concentrations or estimated glomerular filtration rate, but this association attenuated somewhat after adjustment for concentrations of high-density lipoprotein cholesterol and C-reactive protein. The C-index for a CVD risk prediction model containing conventional cardiovascular risk factors alone was 0.7434 (95% CI, 0.7350 to 0.7517). The addition of information on HbA1c was associated with a C-index change of 0.0018 (0.0003 to 0.0033) and a net reclassification improvement of 0.42 (-0.63 to 1.48) for the categories of predicted 10-year CVD risk. The improvement provided by HbA1c assessment in prediction of CVD risk was equal to or better than estimated improvements for measurement of fasting, random, or postload plasma glucose levels. CONCLUSIONS AND RELEVANCE: In a study of individuals without known CVD or diabetes, additional assessment of HbA1c values in the context of CVD risk assessment provided little incremental benefit for prediction of CVD risk.
Keywords: Aged; C-Reactive Protein; Cholesterol, HDL; Coronary Disease; Diabetes Mellitus; Female; Glycated Hemoglobin A; Humans; Male; Middle Aged; Predictive Value of Tests; Prospective Studies; Risk Assessment; Stroke

Identification of novel genetic Loci associated with thyroid peroxidase antibodies and clinical thyroid disease. - Medici, Marco; Porcu, Eleonora; Pistis, Giorgio; Teumer, Alexander; Brown, Suzanne J; Jensen, Richard A; Rawal, Rajesh; Roef, Greet L; Plantinga, Theo S; Vermeulen, Sita H; Lahti, Jari; Simmonds, Matthew J; et al. (PLoS Genet, 2014)
Autoimmune thyroid diseases (AITD) are common, affecting 2-5% of the general population. Individuals with positive thyroid peroxidase antibodies (TPOAbs) have an increased risk of autoimmune hypothyroidism (Hashimoto's thyroiditis), as well as autoimmune hyperthyroidism (Graves' disease). As the possible causative genes of TPOAbs and AITD remain largely unknown, we performed GWAS meta-analyses in 18,297 individuals for TPOAb-positivity (1769 TPOAb-positives and 16,528 TPOAb-negatives) and in 12,353 individuals for TPOAb serum levels, with replication in 8,990 individuals. Significant associations (P<5×10(-8)) were detected at TPO-rs11675434, ATXN2-rs653178, and BACH2-rs10944479 for TPOAb-positivity, and at TPO-rs11675434, MAGI3-rs1230666, and KALRN-rs2010099 for TPOAb levels. Individual and combined effects (genetic risk scores) of these variants on (subclinical) hypo- and hyperthyroidism, goiter and thyroid cancer were studied. Individuals with a high genetic risk score had, besides an increased risk of TPOAb-positivity (OR: 2.18, 95% CI 1.68-2.81, P = 8.1×10(-8)), a higher risk of increased thyroid-stimulating hormone levels (OR: 1.51, 95% CI 1.26-1.82, P = 2.9×10(-6)), as well as a decreased risk of goiter (OR: 0.77, 95% CI 0.66-0.89, P = 6.5×10(-4)). The MAGI3 and BACH2 variants were associated with an increased risk of hyperthyroidism, which was replicated in an independent cohort of patients with Graves' disease (OR: 1.37, 95% CI 1.22-1.54, P = 1.2×10(-7) and OR: 1.25, 95% CI 1.12-1.39, P = 6.2×10(-5)). The MAGI3 variant was also associated with an increased risk of hypothyroidism (OR: 1.57, 95% CI 1.18-2.10, P = 1.9×10(-3)). This first GWAS meta-analysis for TPOAbs identified five newly associated loci, three of which were also associated with clinical thyroid disease. With these markers we identified a large subgroup in the general population with a substantially increased risk of TPOAbs. The results provide insight into why individuals with thyroid autoimmunity do or do not eventually develop thyroid disease, and these markers may therefore predict which TPOAb-positives are particularly at risk of developing clinical thyroid dysfunction.
Keywords: Autoantibodies; Genetic Loci; Genome-Wide Association Study; Graves Disease; Hashimoto Disease; Humans; Iodide Peroxidase; Risk Factors; Thyroiditis, Autoimmune; Thyrotropin

Large multiethnic Candidate Gene Study for C-reactive protein levels: identification of a novel association at CD36 in African Americans. - Ellis, Jaclyn; Lange, Ethan M; Li, Jin; Dupuis, Josée; Baumert, Jens; Walston, Jeremy D; Keating, Brendan J; Durda, Peter; Fox, Ervin R; Palmer, Cameron D; Meng, Yan A; Young, Taylor; et al. (Hum Genet, 2014)
C-reactive protein (CRP) is a heritable biomarker of systemic inflammation and a predictor of cardiovascular disease (CVD). Large-scale genetic association studies for CRP have largely focused on individuals of European descent. We sought to uncover novel genetic variants for CRP in a multiethnic sample using the ITMAT Broad-CARe (IBC) array, a custom 50,000 SNP gene-centric array having dense coverage of over 2,000 candidate CVD genes. We performed analyses on 7,570 African Americans (AA) from the Candidate gene Association Resource (CARe) study and race-combined meta-analyses that included 29,939 additional individuals of European descent from CARe, the Women's Health Initiative (WHI) and KORA studies. We observed array-wide significance (p < 2.2 × 10(-6)) for four loci in AA, three of which have been reported previously in individuals of European descent (IL6R, p = 2.0 × 10(-6); CRP, p = 4.2 × 10(-71); APOE, p = 1.6 × 10(-6)). The fourth significant locus, CD36 (p = 1.6 × 10(-6)), was observed at a functional variant (rs3211938) that is extremely rare in individuals of European descent. We replicated the CD36 finding (p = 1.8 × 10(-5)) in an independent sample of 8,041 AA women from WHI; a meta-analysis combining the CARe and WHI AA results at rs3211938 reached genome-wide significance (p = 1.5 × 10(-10)). In the race-combined meta-analyses, 13 loci reached significance, including ten (CRP, TOMM40/APOE/APOC1, HNF1A, LEPR, GCKR, IL6R, IL1RN, NLRP3, HNF4A and BAZ1B/BCL7B) previously associated with CRP, and one (ARNTL) previously reported to be nominally associated with CRP. Two novel loci were also detected (RPS6KB1, p = 2.0 × 10(-6); CD36, p = 1.4 × 10(-6)). These results highlight both shared and unique genetic risk factors for CRP in AA compared to populations of European descent.
Keywords: Adult; African Americans; Aged; Biomarkers; C-Reactive Protein; Cardiovascular Diseases; CD36 Antigens; Female; Genetic Loci; Genetic Predisposition to Disease; Genetics, Population; Genome-Wide Association Study; Humans; Meta-Analysis as Topic; Middle Aged; Polymorphism, Single Nucleotide; Risk Factors

Large-scale genome-wide association studies and meta-analyses of longitudinal change in adult lung function. - Tang, Wenbo; Kowgier, Matthew; Loth, Daan W; Soler Artigas, Maria; Joubert, Bonnie R; Hodge, Emily; Gharib, Sina A; Smith, Albert V; Ruczinski, Ingo; Gudnason, Vilmundur; Mathias, Rasika A; Harris, Tamara B; et al. (PLoS One, 2014)
BACKGROUND: Genome-wide association studies (GWAS) have identified numerous loci influencing cross-sectional lung function, but less is known about genes influencing longitudinal change in lung function. METHODS: We performed GWAS of the rate of change in forced expiratory volume in the first second (FEV1) in 14 longitudinal, population-based cohort studies comprising 27,249 adults of European ancestry using linear mixed effects model and combined cohort-specific results using fixed effect meta-analysis to identify novel genetic loci associated with longitudinal change in lung function. Gene expression analyses were subsequently performed for identified genetic loci. As a secondary aim, we estimated the mean rate of decline in FEV1 by smoking pattern, irrespective of genotypes, across these 14 studies using meta-analysis. RESULTS: The overall meta-analysis produced suggestive evidence for association at the novel IL16/STARD5/TMC3 locus on chromosome 15 (P  =  5.71 × 10(-7)). In addition, meta-analysis using the five cohorts with ≥3 FEV1 measurements per participant identified the novel ME3 locus on chromosome 11 (P  =  2.18 × 10(-8)) at genome-wide significance. Neither locus was associated with FEV1 decline in two additional cohort studies. We confirmed gene expression of IL16, STARD5, and ME3 in multiple lung tissues. Publicly available microarray data confirmed differential expression of all three genes in lung samples from COPD patients compared with controls. Irrespective of genotypes, the combined estimate for FEV1 decline was 26.9, 29.2 and 35.7 mL/year in never, former, and persistent smokers, respectively. CONCLUSIONS: In this large-scale GWAS, we identified two novel genetic loci in association with the rate of change in FEV1 that harbor candidate genes with biologically plausible functional links to lung function.
Keywords: Adult; Chromosomes, Human, Pair 11; Female; Gene Expression Regulation; Genetic Loci; Genome-Wide Association Study; Humans; Longitudinal Studies; Male; Respiration

Large-scale meta-analysis of genome-wide association data identifies six new risk loci for Parkinson's disease. - Nalls, Mike A; Pankratz, Nathan; Lill, Christina M; Do, Chuong B; Hernandez, Dena G; Saad, Mohamad; DeStefano, Anita L; Kara, Eleanna; Bras, Jose; Sharma, Manu; Schulte, Claudia; Keller, Margaux F; et al. (Nat Genet, 2014)
We conducted a meta-analysis of Parkinson's disease genome-wide association studies using a common set of 7,893,274 variants across 13,708 cases and 95,282 controls. Twenty-six loci were identified as having genome-wide significant association; these and 6 additional previously reported loci were then tested in an independent set of 5,353 cases and 5,551 controls. Of the 32 tested SNPs, 24 replicated, including 6 newly identified loci. Conditional analyses within loci showed that four loci, including GBA, GAK-DGKQ, SNCA and the HLA region, contain a secondary independent risk variant. In total, we identified and replicated 28 independent risk variants for Parkinson's disease across 24 loci. Although the effect of each individual locus was small, risk profile analysis showed substantial cumulative risk in a comparison of the highest and lowest quintiles of genetic risk (odds ratio (OR) = 3.31, 95% confidence interval (CI) = 2.55-4.30; P = 2 × 10(-16)). We also show six risk loci associated with proximal gene expression or DNA methylation.
Keywords: Case-Control Studies; Genetic Loci; Genetic Predisposition to Disease; Genome-Wide Association Study; Genotype; Humans; Parkinson Disease; Polymorphism, Single Nucleotide; Risk Factors

Loss-of-function mutations in APOC3, triglycerides, and coronary disease. - Crosby, Jacy; Peloso, Gina M; Auer, Paul L; Crosslin, David R; Stitziel, Nathan O; Lange, Leslie A; Lu, Yingchang; Tang, Zheng-Zheng; Zhang, He; Hindy, George; Masca, Nicholas; Stirrups, Kathleen; et al. (N Engl J Med, 2014)
BACKGROUND: Plasma triglyceride levels are heritable and are correlated with the risk of coronary heart disease. Sequencing of the protein-coding regions of the human genome (the exome) has the potential to identify rare mutations that have a large effect on phenotype. METHODS: We sequenced the protein-coding regions of 18,666 genes in each of 3734 participants of European or African ancestry in the Exome Sequencing Project. We conducted tests to determine whether rare mutations in coding sequence, individually or in aggregate within a gene, were associated with plasma triglyceride levels. For mutations associated with triglyceride levels, we subsequently evaluated their association with the risk of coronary heart disease in 110,970 persons. RESULTS: An aggregate of rare mutations in the gene encoding apolipoprotein C3 (APOC3) was associated with lower plasma triglyceride levels. Among the four mutations that drove this result, three were loss-of-function mutations: a nonsense mutation (R19X) and two splice-site mutations (IVS2+1G→A and IVS3+1G→T). The fourth was a missense mutation (A43T). Approximately 1 in 150 persons in the study was a heterozygous carrier of at least one of these four mutations. Triglyceride levels in the carriers were 39% lower than levels in noncarriers (P<1×10(-20)), and circulating levels of APOC3 in carriers were 46% lower than levels in noncarriers (P=8×10(-10)). The risk of coronary heart disease among 498 carriers of any rare APOC3 mutation was 40% lower than the risk among 110,472 noncarriers (odds ratio, 0.60; 95% confidence interval, 0.47 to 0.75; P=4×10(-6)). CONCLUSIONS: Rare mutations that disrupt APOC3 function were associated with lower levels of plasma triglycerides and APOC3. Carriers of these mutations were found to have a reduced risk of coronary heart disease. (Funded by the National Heart, Lung, and Blood Institute and others.).
Keywords: African Continental Ancestry Group; Apolipoprotein C-III; Coronary Disease; European Continental Ancestry Group; Exome; Genotype; Heterozygote; Humans; Liver; Mutation; Risk Factors; Sequence Analysis, DNA; Triglycerides

A low-frequency variant in MAPK14 provides mechanistic evidence of a link with myeloperoxidase: a prognostic cardiovascular risk marker. - Waterworth, Dawn M; Li, Li; Scott, Robert; Warren, Liling; Gillson, Christopher; Aponte, Jennifer; Sarov-Blat, Lea; Sprecher, Dennis; Dupuis, Josée; Reiner, Alex; Psaty, Bruce M; Tracy, Russell P; et al. (J Am Heart Assoc, 2014)
BACKGROUND: Genetics can be used to predict drug effects and generate hypotheses around alternative indications. To support Losmapimod, a p38 mitogen-activated protein kinase inhibitor in development for acute coronary syndrome, we characterized gene variation in MAPK11/14 genes by exome sequencing and follow-up genotyping or imputation in participants well-phenotyped for cardiovascular and metabolic traits. METHODS AND RESULTS: Investigation of genetic variation in MAPK11 and MAPK14 genes using additive genetic models in linear or logistic regression with cardiovascular, metabolic, and biomarker phenotypes highlighted an association of RS2859144 in MAPK14 with myeloperoxidase in a dyslipidemic population (Genetic Epidemiology of Metabolic Syndrome Study), P=2.3×10(-6)). This variant (or proxy) was consistently associated with myeloperoxidase in the Framingham Heart Study and Cardiovascular Health Study studies (replication meta-P=0.003), leading to a meta-P value of 9.96×10(-7) in the 3 dyslipidemic groups. The variant or its proxy was then profiled in additional population-based cohorts (up to a total of 58 930 subjects) including Cohorte Lausannoise, Ely, Fenland, European Prospective Investigation of Cancer, London Life Sciences Prospective Population Study, and the Genetics of Obesity Associations study obesity case-control for up to 40 cardiovascular and metabolic traits. Overall analysis identified the same single nucleotide polymorphisms to be nominally associated consistently with glomerular filtration rate (P=0.002) and risk of obesity (body mass index ≥30 kg/m(2), P=0.004). CONCLUSIONS: As myeloperoxidase is a prognostic marker of coronary events, the MAPK14 variant may provide a mechanistic link between p38 map kinase and these events, providing information consistent with current indication of Losmapimod for acute coronary syndrome. If replicated, the association with glomerular filtration rate, along with previous biological findings, also provides support for kidney diseases as alternative indications.
Keywords: Adult; Aged; Cardiovascular Diseases; Dyslipidemias; Exome; Female; Genotype; Humans; Linear Models; Logistic Models; Male; Metabolic Syndrome X; Middle Aged; Mitogen-Activated Protein Kinase 11; Mitogen-Activated Protein Kinase 14; Obesity; Peroxidase; Polymorphism, Single Nucleotide; Prognosis; Risk Factors; Sequence Analysis, DNA

Meta-analysis in more than 17,900 cases of ischemic stroke reveals a novel association at 12q24.12. - Kilarski, Laura L; Achterberg, Sefanja; Devan, William J; Traylor, Matthew; Malik, Rainer; Lindgren, Arne; Pare, Guillame; Sharma, Pankaj; Slowik, Agniesczka; Thijs, Vincent; Walters, Matthew; Worrall, Bradford B; et al. (Neurology, 2014)
OBJECTIVES: To perform a genome-wide association study (GWAS) using the Immunochip array in 3,420 cases of ischemic stroke and 6,821 controls, followed by a meta-analysis with data from more than 14,000 additional ischemic stroke cases. METHODS: Using the Immunochip, we genotyped 3,420 ischemic stroke cases and 6,821 controls. After imputation we meta-analyzed the results with imputed GWAS data from 3,548 cases and 5,972 controls recruited from the ischemic stroke WTCCC2 study, and with summary statistics from a further 8,480 cases and 56,032 controls in the METASTROKE consortium. A final in silico "look-up" of 2 single nucleotide polymorphisms in 2,522 cases and 1,899 controls was performed. Associations were also examined in 1,088 cases with intracerebral hemorrhage and 1,102 controls. RESULTS: In an overall analysis of 17,970 cases of ischemic stroke and 70,764 controls, we identified a novel association on chromosome 12q24 (rs10744777, odds ratio [OR] 1.10 [1.07-1.13], p = 7.12 × 10(-11)) with ischemic stroke. The association was with all ischemic stroke rather than an individual stroke subtype, with similar effect sizes seen in different stroke subtypes. There was no association with intracerebral hemorrhage (OR 1.03 [0.90-1.17], p = 0.695). CONCLUSION: Our results show, for the first time, a genetic risk locus associated with ischemic stroke as a whole, rather than in a subtype-specific manner. This finding was not associated with intracerebral hemorrhage.
Keywords: Brain Ischemia; Cerebral Hemorrhage; Chromosomes, Human, Pair 12; Genetic Predisposition to Disease; Genome-Wide Association Study; Genotype; Humans; Polymorphism, Single Nucleotide; Risk; Stroke

Meta-analysis of genome-wide association studies in African Americans provides insights into the genetic architecture of type 2 diabetes. - Ng, Maggie C Y; Shriner, Daniel; Chen, Brian H; Li, Jiang; Chen, Wei-Min; Guo, Xiuqing; Liu, Jiankang; Bielinski, Suzette J; Yanek, Lisa R; Nalls, Michael A; Comeau, Mary E; Rasmussen-Torvik, Laura J; et al. (PLoS Genet, 2014)
Type 2 diabetes (T2D) is more prevalent in African Americans than in Europeans. However, little is known about the genetic risk in African Americans despite the recent identification of more than 70 T2D loci primarily by genome-wide association studies (GWAS) in individuals of European ancestry. In order to investigate the genetic architecture of T2D in African Americans, the MEta-analysis of type 2 DIabetes in African Americans (MEDIA) Consortium examined 17 GWAS on T2D comprising 8,284 cases and 15,543 controls in African Americans in stage 1 analysis. Single nucleotide polymorphisms (SNPs) association analysis was conducted in each study under the additive model after adjustment for age, sex, study site, and principal components. Meta-analysis of approximately 2.6 million genotyped and imputed SNPs in all studies was conducted using an inverse variance-weighted fixed effect model. Replications were performed to follow up 21 loci in up to 6,061 cases and 5,483 controls in African Americans, and 8,130 cases and 38,987 controls of European ancestry. We identified three known loci (TCF7L2, HMGA2 and KCNQ1) and two novel loci (HLA-B and INS-IGF2) at genome-wide significance (4.15 × 10(-94)<P<5 × 10(-8), odds ratio (OR)  = 1.09 to 1.36). Fine-mapping revealed that 88 of 158 previously identified T2D or glucose homeostasis loci demonstrated nominal to highly significant association (2.2 × 10(-23) < locus-wide P<0.05). These novel and previously identified loci yielded a sibling relative risk of 1.19, explaining 17.5% of the phenotypic variance of T2D on the liability scale in African Americans. Overall, this study identified two novel susceptibility loci for T2D in African Americans. A substantial number of previously reported loci are transferable to African Americans after accounting for linkage disequilibrium, enabling fine mapping of causal variants in trans-ethnic meta-analysis studies.
Keywords: African Americans; Diabetes Mellitus, Type 2; Genome-Wide Association Study; HLA-B27 Antigen; HMGA2 Protein; Humans; KCNQ1 Potassium Channel; Mutant Chimeric Proteins; Polymorphism, Single Nucleotide; Transcription Factor 7-Like 2 Protein

Meta-analysis of loci associated with age at natural menopause in African-American women. - Chen, Christina T L; Liu, Ching-Ti; Chen, Gary K; Andrews, Jeanette S; Arnold, Alice M; Dreyfus, Jill; Franceschini, Nora; Garcia, Melissa E; Kerr, Kathleen F; Li, Guo; Lohman, Kurt K; Musani, Solomon K; et al. (Hum Mol Genet, 2014)
Age at menopause marks the end of a woman's reproductive life and its timing associates with risks for cancer, cardiovascular and bone disorders. GWAS and candidate gene studies conducted in women of European ancestry have identified 27 loci associated with age at menopause. The relevance of these loci to women of African ancestry has not been previously studied. We therefore sought to uncover additional menopause loci and investigate the relevance of European menopause loci by performing a GWAS meta-analysis in 6510 women with African ancestry derived from 11 studies across the USA. We did not identify any additional loci significantly associated with age at menopause in African Americans. We replicated the associations between six loci and age at menopause (P-value < 0.05): AMHR2, RHBLD2, PRIM1, HK3/UMC1, BRSK1/TMEM150B and MCM8. In addition, associations of 14 loci are directionally consistent with previous reports. We provide evidence that genetic variants influencing reproductive traits identified in European populations are also important in women of African ancestry residing in USA.
Keywords: African Americans; Age Factors; Chromosomes, Human; European Continental Ancestry Group; Female; Genetic Loci; Genetic Variation; Genome-Wide Association Study; Humans; Menopause; United States

Multiancestral analysis of inflammation-related genetic variants and C-reactive protein in the population architecture using genomics and epidemiology study. - Kocarnik, Jonathan M; Pendergrass, Sarah A; Carty, Cara L; Pankow, James S; Schumacher, Fredrick R; Cheng, Iona; Durda, Peter; Ambite, Jose Luis; Deelman, Ewa; Cook, Nancy R; Liu, Simin; Wactawski-Wende, Jean; et al. (Circ Cardiovasc Genet, 2014)
BACKGROUND: C-reactive protein (CRP) is a biomarker of inflammation. Genome-wide association studies (GWAS) have identified single-nucleotide polymorphisms (SNPs) associated with CRP concentrations and inflammation-related traits such as cardiovascular disease, type 2 diabetes mellitus, and obesity. We aimed to replicate previous CRP-SNP associations, assess whether these associations generalize to additional race/ethnicity groups, and evaluate inflammation-related SNPs for a potentially pleiotropic association with CRP. METHODS AND RESULTS: We selected and analyzed 16 CRP-associated and 250 inflammation-related GWAS SNPs among 40 473 African American, American Indian, Asian/Pacific Islander, European American, and Hispanic participants from 7 studies collaborating in the Population Architecture using Genomics and Epidemiology (PAGE) study. Fixed-effect meta-analyses combined study-specific race/ethnicity-stratified linear regression estimates to evaluate the association between each SNP and high-sensitivity CRP. Overall, 18 SNPs in 8 loci were significantly associated with CRP (Bonferroni-corrected P<3.1×10(-3) for replication, P<2.0×10(-4) for pleiotropy): Seven of these were specific to European Americans, while 9 additionally generalized to African Americans (1), Hispanics (5), or both (3); 1 SNP was seen only in African Americans and Hispanics. Two SNPs in the CELSR2/PSRC1/SORT1 locus showed a potentially novel association with CRP: rs599839 (P=2.0×10(-6)) and rs646776 (P=3.1×10(-5)). CONCLUSIONS: We replicated 16 SNP-CRP associations, 10 of which generalized to African Americans and/or Hispanics. We also identified potentially novel pleiotropic associations with CRP for two SNPs previously associated with coronary artery disease and/or low-density lipoprotein-cholesterol. These findings demonstrate the benefit of evaluating genotype-phenotype associations in multiple race/ethnicity groups and looking for pleiotropic relationships among SNPs previously associated with related phenotypes.
Keywords: Adult; African Continental Ancestry Group; Aged; Asian Continental Ancestry Group; C-Reactive Protein; Female; Genetic Variation; Genome-Wide Association Study; Hispanic Americans; Humans; Indians, North American; Inflammation; Male; Middle Aged; Polymorphism, Single Nucleotide; United States; Young Adult

Multilocus genetic risk score associates with ischemic stroke in case-control and prospective cohort studies. - Malik, Rainer; Bevan, Steve; Nalls, Michael A; Holliday, Elizabeth G; Devan, William J; Cheng, Yu-Ching; Ibrahim-Verbaas, Carla A; Verhaaren, Benjamin F J; Bis, Joshua C; Joon, Aron Y; de Stefano, Anita L; Fornage, Myriam; et al. (Stroke, 2014)
BACKGROUND AND PURPOSE: Genome-wide association studies have revealed multiple common variants associated with known risk factors for ischemic stroke (IS). However, their aggregate effect on risk is uncertain. We aimed to generate a multilocus genetic risk score (GRS) for IS based on genome-wide association studies data from clinical-based samples and to establish its external validity in prospective population-based cohorts. METHODS: Three thousand five hundred forty-eight clinic-based IS cases and 6399 controls from the Wellcome Trust Case Control Consortium 2 were used for derivation of the GRS. Subjects from the METASTROKE consortium served as a replication sample. The validation sample consisted of 22 751 participants from the Cohorts for Heart and Aging Research in Genomic Epidemiology consortium. We selected variants that had reached genome-wide significance in previous association studies on established risk factors for IS. RESULTS: A combined GRS for atrial fibrillation, coronary artery disease, hypertension, and systolic blood pressure significantly associated with IS both in the case-control samples and in the prospective population-based studies. Subjects in the top quintile of the combined GRS had >2-fold increased risk of IS compared with subjects in the lowest quintile. Addition of the combined GRS to a simple model based on sex significantly improved the prediction of IS in the combined clinic-based samples but not in the population-based studies, and there was no significant improvement in net reclassification. CONCLUSIONS: A multilocus GRS based on common variants for established cardiovascular risk factors was significantly associated with IS both in clinic-based samples and in the general population. However, the improvement in clinical risk prediction was found to be small.
Keywords: Adult; Aged; Aged, 80 and over; Atrial Fibrillation; Blood Pressure; Brain Ischemia; Case-Control Studies; Cohort Studies; Coronary Artery Disease; Female; Genetic Predisposition to Disease; Genetic Variation; Genome-Wide Association Study; Humans; Hypertension; Male; Middle Aged; Multilocus Sequence Typing; Polymorphism, Single Nucleotide; Population; Prospective Studies; Reproducibility of Results; Risk Assessment; Risk Factors; Sex Factors; Stroke

No evidence for genome-wide interactions on plasma fibrinogen by smoking, alcohol consumption and body mass index: results from meta-analyses of 80,607 subjects. - Baumert, Jens; Huang, Jie; McKnight, Barbara; Sabater-Lleal, Maria; Steri, Maristella; Chu, Audrey Y; Trompet, Stella; Lopez, Lorna M; Fornage, Myriam; Teumer, Alexander; Tang, Weihong; Rudnicka, Alicja R; et al. (PLoS One, 2014)
Plasma fibrinogen is an acute phase protein playing an important role in the blood coagulation cascade having strong associations with smoking, alcohol consumption and body mass index (BMI). Genome-wide association studies (GWAS) have identified a variety of gene regions associated with elevated plasma fibrinogen concentrations. However, little is yet known about how associations between environmental factors and fibrinogen might be modified by genetic variation. Therefore, we conducted large-scale meta-analyses of genome-wide interaction studies to identify possible interactions of genetic variants and smoking status, alcohol consumption or BMI on fibrinogen concentration. The present study included 80,607 subjects of European ancestry from 22 studies. Genome-wide interaction analyses were performed separately in each study for about 2.6 million single nucleotide polymorphisms (SNPs) across the 22 autosomal chromosomes. For each SNP and risk factor, we performed a linear regression under an additive genetic model including an interaction term between SNP and risk factor. Interaction estimates were meta-analysed using a fixed-effects model. No genome-wide significant interaction with smoking status, alcohol consumption or BMI was observed in the meta-analyses. The most suggestive interaction was found for smoking and rs10519203, located in the LOC123688 region on chromosome 15, with a p value of 6.2 × 10(-8). This large genome-wide interaction study including 80,607 participants found no strong evidence of interaction between genetic variants and smoking status, alcohol consumption or BMI on fibrinogen concentrations. Further studies are needed to yield deeper insight in the interplay between environmental factors and gene variants on the regulation of fibrinogen concentrations.
Keywords: Alcohol Drinking; Body Mass Index; Fibrinogen; Gene-Environment Interaction; Genomics; Humans; Smoking

Novel gene variants predict serum levels of the cytokines IL-18 and IL-1ra in older adults. - Matteini, A M; Li, J; Lange, E M; Tanaka, T; Lange, L A; Tracy, R P; Wang, Y; Biggs, M L; Arking, D E; Fallin, M D; Chakravarti, A; Psaty, B M; et al. (Cytokine, 2014)
Activation of inflammatory pathways measured by serum inflammatory markers such as interleukin-18 (IL-18) and interleukin-1 receptor antagonist (IL-1ra) is strongly associated with the progression of chronic disease states in older adults. Given that these serum cytokine levels are in part a heritable trait, genetic variation may predict increased serum levels. Using the Cardiovascular Health Study and InCHIANTI cohorts, a genome-wide association study was performed to identify genetic variants that influence IL-18 and IL-1ra serum levels among older adults. Multiple linear regression models characterized the association between each SNP and log-transformed cytokine values. Tests for multiple independent signals within statistically significant loci were performed using haplotype analysis and regression models conditional on lead SNP in each region. Multiple SNPs were associated with these cytokines with genome-wide significance, including SNPs in the IL-18-BCO gene region of chromosome 2 for IL-18 (top SNP rs2250417, P=1.9×10(-32)) and in the IL-1 gene family region of chromosome 2 for IL-1ra (rs6743376, P=2.3×10(-26)). Haplotype tests and conditional linear regression models showed evidence of multiple independent signals in these regions. Serum IL-18 levels were also associated with a region on chromosome 2 containing the NLRC4 gene (rs12989936, P=2.7×10(-19)). These data characterize multiple robust genetic signals that influence IL-18 and IL-1ra cytokine production. In particular, the signal for serum IL-18 located on chromosome two is novel and potentially important in inflammasome triggered chronic activation of inflammation in older adults. Replication in independent cohorts is an important next step, as well as molecular studies to better understand the role of NLRC4.
Keywords: Aged; Aged, 80 and over; Calcium-Binding Proteins; CARD Signaling Adaptor Proteins; Chromosomes, Human, Pair 2; Female; Genetic Variation; Genome-Wide Association Study; Genotype; Haplotypes; Humans; Inflammation; Interleukin 1 Receptor Antagonist Protein; Interleukin-18; Male; Polymorphism, Single Nucleotide

Novel genetic markers associate with atrial fibrillation risk in Europeans and Japanese. - Lubitz, Steven A; Lunetta, Kathryn L; Lin, Honghuang; Arking, Dan E; Trompet, Stella; Li, Guo; Krijthe, Bouwe P; Chasman, Daniel I; Barnard, John; Kleber, Marcus E; Dörr, Marcus; Ozaki, Kouichi; et al. (J Am Coll Cardiol, 2014)
OBJECTIVES: This study sought to identify nonredundant atrial fibrillation (AF) genetic susceptibility signals and examine their cumulative relations with AF risk. BACKGROUND: AF-associated loci span broad genomic regions that may contain multiple susceptibility signals. Whether multiple signals exist at AF loci has not been systematically explored. METHODS: We performed association testing conditioned on the most significant, independently associated genetic markers at 9 established AF loci using 2 complementary techniques in 64,683 individuals of European ancestry (3,869 incident and 3,302 prevalent AF cases). Genetic risk scores were created and tested for association with AF in Europeans and an independent sample of 11,309 individuals of Japanese ancestry (7,916 prevalent AF cases). RESULTS: We observed at least 4 distinct AF susceptibility signals on chromosome 4q25 upstream of PITX2, but not at the remaining 8 AF loci. A multilocus score comprised 12 genetic markers demonstrated an estimated 5-fold gradient in AF risk. We observed a similar spectrum of risk associated with these markers in Japanese. Regions containing AF signals on chromosome 4q25 displayed a greater degree of evolutionary conservation than the remainder of the locus, suggesting that they may tag regulatory elements. CONCLUSIONS: The chromosome 4q25 AF locus is architecturally complex and harbors at least 4 AF susceptibility signals in individuals of European ancestry. Similar polygenic AF susceptibility exists between Europeans and Japanese. Future work is necessary to identify causal variants, determine mechanisms by which associated loci predispose to AF, and explore whether AF susceptibility signals classify individuals at risk for AF and related morbidity.
Keywords: Adult; Aged; Aged, 80 and over; Asian Continental Ancestry Group; Atrial Fibrillation; Chromosome Mapping; Chromosomes, Human, Pair 4; Europe; European Continental Ancestry Group; Female; Genetic Markers; Genetic Predisposition to Disease; Homeodomain Proteins; Humans; Japan; Male; Middle Aged; Polymorphism, Single Nucleotide; Transcription Factors

Pharmacogenetic meta-analysis of genome-wide association studies of LDL cholesterol response to statins. - Postmus, Iris; Trompet, Stella; Deshmukh, Harshal A; Barnes, Michael R; Li, Xiaohui; Warren, Helen R; Chasman, Daniel I; Zhou, Kaixin; Arsenault, Benoit J; Donnelly, Louise A; Wiggins, Kerri L; Avery, Christy L; et al. (Nat Commun, 2014)
Statins effectively lower LDL cholesterol levels in large studies and the observed interindividual response variability may be partially explained by genetic variation. Here we perform a pharmacogenetic meta-analysis of genome-wide association studies (GWAS) in studies addressing the LDL cholesterol response to statins, including up to 18,596 statin-treated subjects. We validate the most promising signals in a further 22,318 statin recipients and identify two loci, SORT1/CELSR2/PSRC1 and SLCO1B1, not previously identified in GWAS. Moreover, we confirm the previously described associations with APOE and LPA. Our findings advance the understanding of the pharmacogenetic architecture of statin response.
Keywords: Cholesterol, LDL; Genome-Wide Association Study; Humans; Hydroxymethylglutaryl-CoA Reductase Inhibitors; Pharmacogenetics; Polymorphism, Single Nucleotide

Plasma phospholipid saturated fatty acids and incident atrial fibrillation: the Cardiovascular Health Study. - Fretts, Amanda M; Mozaffarian, Dariush; Siscovick, David S; Djoussé, Luc; Heckbert, Susan R; King, Irena B; McKnight, Barbara; Sitlani, Colleen; Sacks, Frank M; Song, Xiaoling; Sotoodehnia, Nona; Spiegelman, Donna; et al. (J Am Heart Assoc, 2014)
BACKGROUND: Prior studies suggest that circulating fatty acids may influence the risk of atrial fibrillation (AF), but little is known about the associations of circulating saturated fatty acids with risk of AF. METHODS AND RESULTS: The study population included 2899 participants from the Cardiovascular Health Study, a community-based longitudinal cohort of adults aged 65 years or older in the United States who were free of prevalent coronary heart disease and AF in 1992. Cox regression was used to assess the association of all the long-chain saturated fatty acids-palmitic acid (16:0), stearic acid (18:0), arachidic acid (20:0), behenic acid (22:0), and lignoceric acid (24:0)-with incident AF. During a median of 11.2 years of follow-up, 707 cases of incident AF occurred. After adjustment for other AF risk factors, higher levels of circulating 16:0 were associated with a higher risk of AF (hazard ratio comparing highest and lowest quartiles: 1.48; 95% CI: 1.18, 1.86). In contrast, higher levels of circulating 18:0, 20:0, 22:0, and 24:0 were each associated with a lower risk of AF. The hazard ratios (95% CI) for AF in the top and bottom quartiles were 0.76 (95% CI: 0.61, 0.95) for 18:0; 0.78 (95% CI: 0.63, 0.97) for 20:0; 0.62 (95% CI: 0.50, 0.78) for 22:0; and 0.68 (95% CI: 0.55, 0.85) for 24:0. CONCLUSIONS: Results from this prospective cohort study of older adults demonstrate divergent associations of circulating 16:0 versus longer-chain saturated fatty acids with incident AF, highlighting the need to investigate both determinants of these levels and potential pathways of the observed differential risk.
Keywords: Aged; Aged, 80 and over; Atrial Fibrillation; Eicosanoic Acids; Fatty Acids; Female; Humans; Longitudinal Studies; Male; Palmitic Acid; Phospholipids; Proportional Hazards Models; Prospective Studies; Risk Factors; Stearic Acids; United States

Plasma phospholipid trans-fatty acids levels, cardiovascular diseases, and total mortality: the cardiovascular health study. - Wang, Qianyi; Imamura, Fumiaki; Lemaitre, Rozenn N; Rimm, Eric B; Wang, Molin; King, Irena B; Song, Xiaoling; Siscovick, David; Mozaffarian, Dariush (J Am Heart Assoc, 2014)
BACKGROUND: While self-reported trans-fatty acid (TFA) consumption is linked to coronary heart disease (CHD), relationships between objective biomarkers of TFA subtypes (t-16:1n9, total t-18:1, and cis/trans-(c/t-), t/c- and t/t-18:2) and cardiovascular disease (CVD) or total mortality are not well established. METHODS AND RESULTS: We evaluated 2742 adults in the Cardiovascular Health Study, aged 74±5 years and free of prevalent CVD, with plasma phospholipid TFA measures in 1992. Incident fatal and nonfatal CHD events, CVD and non-CVD mortality, and total mortality were centrally adjudicated through 2010. Risks were assessed using Cox proportional hazards. During 31 494 person-years, 1735 total deaths and 639 total CHD events occurred. In the multivariate model including mutual adjustment for the 5 TFA subtypes, circulating t/t-18:2 was associated with higher total mortality (extreme quintile hazard ratio (HR)=1.23, 95% CI=1.04 to 1.44, P-trend=0.01), CVD mortality (HR=1.40, 95% CI=1.05 to 1.86, P-trend=0.02), and total CHD (HR=1.39, 95% CI=1.06 to 1.83, P-trend=0.01). t/c-18:2 was positively related to total mortality (HR=1.19, P-trend=0.05), total CHD (HR=1.67, P-trend=0.002), and nonfatal CHD (HR=2.06, P-trend=0.002) after mutual adjustment; these associations were insignificant without mutual adjustment. Neither t-16:1n9 nor t-18:1 was significantly associated with total mortality or CVD, nor was c/t-18:2 if we excluded early cases. CONCLUSIONS: Among circulating TFAs, t/t-18:2 was most adversely associated with total mortality, mainly due to the increased risk of CVD. t/c-18:2 was also positively associated with total mortality and CHD, but only after adjustment for other TFAs. These results highlight the need for further investigation of dietary sources, nondietary determinants, and health effects of specific TFA subtypes, especially t-18:2 isomers.
Keywords: Aged; Aged, 80 and over; Biomarkers; Cardiovascular Diseases; Cohort Studies; Dietary Fats; Female; Follow-Up Studies; Humans; Incidence; Male; Mortality; Phospholipids; Prognosis; Proportional Hazards Models; Prospective Studies; Trans Fatty Acids

Predicting stroke through genetic risk functions: the CHARGE Risk Score Project. - Ibrahim-Verbaas, Carla A; Fornage, Myriam; Bis, Joshua C; Choi, Seung Hoan; Psaty, Bruce M; Meigs, James B; Rao, Madhu; Nalls, Mike; Fontes, João D; O'Donnell, Christopher J; Kathiresan, Sekar; Ehret, Georg B; et al. (Stroke, 2014)
BACKGROUND AND PURPOSE: Beyond the Framingham Stroke Risk Score, prediction of future stroke may improve with a genetic risk score (GRS) based on single-nucleotide polymorphisms associated with stroke and its risk factors. METHODS: The study includes 4 population-based cohorts with 2047 first incident strokes from 22,720 initially stroke-free European origin participants aged ≥55 years, who were followed for up to 20 years. GRSs were constructed with 324 single-nucleotide polymorphisms implicated in stroke and 9 risk factors. The association of the GRS to first incident stroke was tested using Cox regression; the GRS predictive properties were assessed with area under the curve statistics comparing the GRS with age and sex, Framingham Stroke Risk Score models, and reclassification statistics. These analyses were performed per cohort and in a meta-analysis of pooled data. Replication was sought in a case-control study of ischemic stroke. RESULTS: In the meta-analysis, adding the GRS to the Framingham Stroke Risk Score, age and sex model resulted in a significant improvement in discrimination (all stroke: Δjoint area under the curve=0.016, P=2.3×10(-6); ischemic stroke: Δjoint area under the curve=0.021, P=3.7×10(-7)), although the overall area under the curve remained low. In all the studies, there was a highly significantly improved net reclassification index (P<10(-4)). CONCLUSIONS: The single-nucleotide polymorphisms associated with stroke and its risk factors result only in a small improvement in prediction of future stroke compared with the classical epidemiological risk factors for stroke.
Keywords: Age Factors; Aged; Aged, 80 and over; Area Under Curve; Case-Control Studies; Cohort Studies; European Continental Ancestry Group; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Genotype; Humans; Male; Middle Aged; Polymorphism, Single Nucleotide; Regression Analysis; Risk Factors; ROC Curve; Sex Factors; Stroke

Quantifying rare, deleterious variation in 12 human cytochrome P450 drug-metabolism genes in a large-scale exome dataset. - Gordon, Adam S; Tabor, Holly K; Johnson, Andrew D; Snively, Beverly M; Assimes, Themistocles L; Auer, Paul L; Ioannidis, John P A; Peters, Ulrike; Robinson, Jennifer G; Sucheston, Lara E; Wang, Danxin; Sotoodehnia, Nona; et al. (Hum Mol Genet, 2014)
The study of genetic influences on drug response and efficacy ('pharmacogenetics') has existed for over 50 years. Yet, we still lack a complete picture of how genetic variation, both common and rare, affects each individual's responses to medications. Exome sequencing is a promising alternative method for pharmacogenetic discovery as it provides information on both common and rare variation in large numbers of individuals. Using exome data from 2203 AA and 4300 Caucasian individuals through the NHLBI Exome Sequencing Project, we conducted a survey of coding variation within 12 Cytochrome P450 (CYP) genes that are collectively responsible for catalyzing nearly 75% of all known Phase I drug oxidation reactions. In addition to identifying many polymorphisms with known pharmacogenetic effects, we discovered over 730 novel nonsynonymous alleles across the 12 CYP genes of interest. These alleles include many with diverse functional effects such as premature stop codons, aberrant splicesites and mutations at conserved active site residues. Our analysis considering both novel, predicted functional alleles as well as known, actionable CYP alleles reveals that rare, deleterious variation contributes markedly to the overall burden of pharmacogenetic alleles within the populations considered, and that the contribution of rare variation to this burden is over three times greater in AA individuals as compared with Caucasians. While most of these impactful alleles are individually rare, 7.6-11.7% of individuals interrogated in the study carry at least one newly described potentially deleterious alleles in a major drug-metabolizing CYP.
Keywords: Cytochrome P-450 Enzyme System; Databases, Genetic; European Continental Ancestry Group; Exome; Humans; Pharmaceutical Preparations; Pharmacogenetics; Polymorphism, Genetic

Relative risks of chronic kidney disease for mortality and end-stage renal disease across races are similar. - Wen, Chi Pang; Matsushita, Kunihiro; Coresh, Josef; Iseki, Kunitoshi; Islam, Muhammad; Katz, Ronit; McClellan, William; Peralta, Carmen A; Wang, Haiyan; de Zeeuw, Dick; Astor, Brad C; Gansevoort, Ron T; et al. (Kidney Int, 2014)
Some suggest race-specific cutpoints for kidney measures to define and stage chronic kidney disease (CKD), but evidence for race-specific clinical impact is limited. To address this issue, we compared hazard ratios of estimated glomerular filtration rates (eGFR) and albuminuria across races using meta-regression in 1.1 million adults (75% Asians, 21% Whites, and 4% Blacks) from 45 cohorts. Results came mainly from 25 general population cohorts comprising 0.9 million individuals. The associations of lower eGFR and higher albuminuria with mortality and end-stage renal disease (ESRD) were largely similar across races. For example, in Asians, Whites, and Blacks, the adjusted hazard ratios (95% confidence interval) for eGFR 45-59 versus 90-104 ml/min per 1.73 m(2) were 1.3 (1.2-1.3), 1.1 (1.0-1.2), and 1.3 (1.1-1.7) for all-cause mortality, 1.6 (1.5-1.7), 1.4 (1.2-1.7), and 1.4 (0.7-2.9) for cardiovascular mortality, and 27.6 (11.1-68.7), 11.2 (6.0-20.9), and 4.1 (2.2-7.5) for ESRD, respectively. The corresponding hazard ratios for urine albumin-to-creatinine ratio 30-299 mg/g or dipstick 1+ versus an albumin-to-creatinine ratio under 10 or dipstick negative were 1.6 (1.4-1.8), 1.7 (1.5-1.9), and 1.8 (1.7-2.1) for all-cause mortality, 1.7 (1.4-2.0), 1.8 (1.5-2.1), and 2.8 (2.2-3.6) for cardiovascular mortality, and 7.4 (2.0-27.6), 4.0 (2.8-5.9), and 5.6 (3.4-9.2) for ESRD, respectively. Thus, the relative mortality or ESRD risks of lower eGFR and higher albuminuria were largely similar among three major races, supporting similar clinical approach to CKD definition and staging, across races.
Keywords: Adult; African Continental Ancestry Group; Aged; Aged, 80 and over; Albuminuria; Asian Continental Ancestry Group; Cardiovascular Diseases; Cohort Studies; Creatinine; European Continental Ancestry Group; Female; Glomerular Filtration Rate; Humans; Kidney Failure, Chronic; Male; Middle Aged; Odds Ratio; Renal Insufficiency, Chronic; Risk Factors

Risk factors for cardiovascular disease across the spectrum of older age: the Cardiovascular Health Study. - Odden, Michelle C; Shlipak, Michael G; Whitson, Heather E; Katz, Ronit; Kearney, Patricia M; deFilippi, Chris; Shastri, Shani; Sarnak, Mark J; Siscovick, David S; Cushman, Mary; Psaty, Bruce M; Newman, Anne B (Atherosclerosis, 2014)
OBJECTIVE: The associations of some risk factors with cardiovascular disease (CVD) are attenuated in older age; whereas others appear robust. The present study aimed to compare CVD risk factors across older age. METHODS: Participants (n = 4883) in the Cardiovascular Health Study free of prevalent CVD, were stratified into three age groups: 65-74, 75-84, 85+ years. Traditional risk factors included systolic blood pressure (BP), LDL-cholesterol, HDL-cholesterol, obesity, and diabetes. Novel risk factors included kidney function, C-reactive protein (CRP), and N-terminal pro-B-type natriuretic peptide (NT pro-BNP). RESULTS: There were 1498 composite CVD events (stroke, myocardial infarction, and cardiovascular death) over 5 years. The associations of high systolic BP and diabetes appeared strongest, though both were attenuated with age (p-values for interaction = 0.01 and 0.002, respectively). The demographic-adjusted hazard ratios (HR) for elevated systolic BP were 1.79 (95% confidence interval: 1.49, 2.15), 1.59 (1.37, 1.85) and 1.10 (0.86, 1.41) in participants aged 65-74, 75-84, 85+, and for diabetes, 2.36 (1.89, 2.95), 1.55 (1.27, 1.89), 1.51 (1.10, 2.09). The novel risk factors had consistent associations with the outcome across the age spectrum; low kidney function: 1.69 (1.31, 2.19), 1.61 (1.36, 1.90), and 1.57 (1.16, 2.14) for 65-74, 75-84, and 85+ years, respectively; elevated CRP: 1.54 (1.28, 1.87), 1.33 (1.13, 1.55), and 1.51 (1.15, 1.97); elevated NT pro-BNP: 2.67 (1.96, 3.64), 2.71 (2.25, 3.27), and 2.18 (1.43, 3.45). CONCLUSIONS: The associations of most traditional risk factors with CVD were minimal in the oldest old, whereas diabetes, eGFR, CRP, and NT pro-BNP were associated with CVD across older age.
Keywords: Aged; Aged, 80 and over; Blood Pressure; C-Reactive Protein; Cardiovascular Diseases; Cholesterol, HDL; Cholesterol, LDL; Diabetes Complications; Diabetes Mellitus; Female; Humans; Inflammation; Kidney; Kidney Diseases; Lipids; Male; Natriuretic Peptide, Brain; Obesity; Peptide Fragments; Risk Factors

A robust method for genome-wide association meta-analysis with the application to circulating insulin-like growth factor I concentrations. - Wang, Tao; Zhou, Baiyu; Guo, Tingwei; Bidlingmaier, Martin; Wallaschofski, Henri; Teumer, Alexander; Vasan, Ramachandran S; Kaplan, Robert C (Genet Epidemiol, 2014)
Genome-wide association studies (GWAS) offer an excellent opportunity to identify the genetic variants underlying complex human diseases. Successful utilization of this approach requires a large sample size to identify single nucleotide polymorphisms (SNPs) with subtle effects. Meta-analysis is a cost-efficient means to achieve large sample size by combining data from multiple independent GWAS; however, results from studies performed on different populations can be variable due to various reasons, including varied linkage equilibrium structures as well as gene-gene and gene-environment interactions. Nevertheless, one should expect effects of the SNP are more similar between similar populations than those between populations with quite different genetic and environmental backgrounds. Prior information on populations of GWAS is often not considered in current meta-analysis methods, rendering such analyses less optimal for the detecting association. This article describes a test that improves meta-analysis to incorporate variable heterogeneity among populations. The proposed method is remarkably simple in computation and hence can be performed in a rapid fashion in the setting of GWAS. Simulation results demonstrate the validity and higher power of the proposed method over conventional methods in the presence of heterogeneity. As a demonstration, we applied the test to real GWAS data to identify SNPs associated with circulating insulin-like growth factor I concentrations.
Keywords: Computer Simulation; Genetic Linkage; Genome; Genome-Wide Association Study; Humans; Insulin-Like Growth Factor I; Meta-Analysis as Topic; Models, Genetic; Polymorphism, Single Nucleotide; Sample Size

A self-report risk index to predict occurrence of dementia in three independent cohorts of older adults: the ANU-ADRI. - Anstey, Kaarin J; Cherbuin, Nicolas; Herath, Pushpani M; Qiu, Chengxuan; Kuller, Lewis H; Lopez, Oscar L; Wilson, Robert S; Fratiglioni, Laura (PLoS One, 2014)
BACKGROUND AND AIMS: The Australian National University AD Risk Index (ANU-ADRI, http://anuadri.anu.edu.au) is a self-report risk index developed using an evidence-based medicine approach to measure risk of Alzheimer's disease (AD). We aimed to evaluate the extent to which the ANU-ADRI can predict the risk of AD in older adults and to compare the ANU-ADRI to the dementia risk index developed from the Cardiovascular Risk Factors, Aging and Dementia (CAIDE) study for middle-aged cohorts. METHODS: This study included three validation cohorts, i.e., the Rush Memory and Aging Study (MAP) (n = 903, age ≥53 years), the Kungsholmen Project (KP) (n = 905, age ≥75 years), and the Cardiovascular Health Cognition Study (CVHS) (n = 2496, age ≥65 years) that were each followed for dementia. Baseline data were collected on exposure to the 15 risk factors included in the ANU-ADRI of which MAP had 10, KP had 8 and CVHS had 9. Risk scores and C-statistics were computed for individual participants for the ANU-ADRI and the CAIDE index. RESULTS: For the ANU-ADRI using available data, the MAP study c-statistic was 0·637 (95% CI 0·596-0·678), for the KP study it was 0·740 (0·712-0·768) and for the CVHS it was 0·733 (0·691-0·776) for predicting AD. When a common set of risk and protective factors were used c-statistics were 0.689 (95% CI 0.650-0.727), 0.666 (0.628-0.704) and 0.734 (0.707-0.761) for MAP, KP and CVHS respectively. Results for CAIDE ranged from c-statistics of 0.488 (0.427-0.554) to 0.595 (0.565-0.625). CONCLUSION: A composite risk score derived from the ANU-ADRI weights including 8-10 risk or protective factors is a valid, self-report tool to identify those at risk of AD and dementia. The accuracy can be further improved in studies including more risk factors and younger cohorts with long-term follow-up.
Keywords: Adult; Aged; Aged, 80 and over; Alzheimer Disease; Dementia; Female; Humans; Incidence; Male; Middle Aged; Risk; ROC Curve; Self Report

Separate prediction of intracerebral hemorrhage and ischemic stroke. - Ferket, Bart S; van Kempen, Bob J H; Wieberdink, Renske G; Steyerberg, Ewout W; Koudstaal, Peter J; Hofman, Albert; Shahar, Eyal; Gottesman, Rebecca F; Rosamond, Wayne; Kizer, Jorge R; Kronmal, Richard A; Psaty, Bruce M; et al. (Neurology, 2014)
OBJECTIVES: To develop and validate 10-year cumulative incidence functions of intracerebral hemorrhage (ICH) and ischemic stroke (IS). METHODS: We used data on 27,493 participants from 3 population-based cohort studies: the Atherosclerosis Risk in Communities Study, median age 54 years, 45% male, median follow-up 20.7 years; the Rotterdam Study, median age 68 years, 38% male, median follow-up 14.3 years; and the Cardiovascular Health Study, median age 71 years, 41% male, median follow-up 12.8 years. Among these participants, 325 ICH events, 2,559 IS events, and 9,909 nonstroke deaths occurred. We developed 10-year cumulative incidence functions for ICH and IS using stratified Cox regression and competing risks analysis. Basic models including only established nonlaboratory risk factors were extended with diastolic blood pressure, total cholesterol/high-density lipoprotein cholesterol ratio, body mass index, waist-to-hip ratio, and glomerular filtration rate. The cumulative incidence functions' performances were cross-validated in each cohort separately by Harrell C-statistic and calibration plots. RESULTS: High total cholesterol/high-density lipoprotein cholesterol ratio decreased the ICH rates but increased IS rates (p for difference across stroke types <0.001). For both the ICH and IS models, C statistics increased more by model extension in the Atherosclerosis Risk in Communities and Cardiovascular Health Study cohorts. Improvements in C statistics were reproduced by cross-validation. Models were well calibrated in all cohorts. Correlations between 10-year ICH and IS risks were moderate in each cohort. CONCLUSIONS: We developed and cross-validated cumulative incidence functions for separate prediction of 10-year ICH and IS risk. These functions can be useful to further specify an individual's stroke risk.
Keywords: Aged; Aged, 80 and over; Atherosclerosis; Body Mass Index; Brain Ischemia; Cholesterol; Female; Humans; Incidence; Intracranial Hemorrhages; Male; Middle Aged; Models, Statistical; Predictive Value of Tests; Risk Assessment; Risk Factors; Stroke

Sequence variation in TMEM18 in association with body mass index: Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) Consortium Targeted Sequencing Study. - Liu, Ching-Ti; Young, Kristin L; Brody, Jennifer A; Olden, Matthias; Wojczynski, Mary K; Heard-Costa, Nancy; Li, Guo; Morrison, Alanna C; Muzny, Donna; Gibbs, Richard A; Reid, Jeffrey G; Shao, Yaming; et al. (Circ Cardiovasc Genet, 2014)
BACKGROUND: Genome-wide association studies for body mass index (BMI) previously identified a locus near TMEM18. We conducted targeted sequencing of this region to investigate the role of common, low-frequency, and rare variants influencing BMI. METHODS AND RESULTS: We sequenced TMEM18 and regions downstream of TMEM18 on chromosome 2 in 3976 individuals of European ancestry from 3 community-based cohorts (Atherosclerosis Risk in Communities, Cardiovascular Health Study, and Framingham Heart Study), including 200 adults selected for high BMI. We examined the association between BMI and variants identified in the region from nucleotide position 586 432 to 677 539 (hg18). Rare variants (minor allele frequency, <1%) were analyzed using a burden test and the sequence kernel association test. Results from the 3 cohort studies were meta-analyzed. We estimate that mean BMI is 0.43 kg/m(2) higher for each copy of the G allele of single-nucleotide polymorphism rs7596758 (minor allele frequency, 29%; P=3.46×10(-4)) using a Bonferroni threshold of P<4.6×10(-4). Analyses conditional on previous genome-wide association study single-nucleotide polymorphisms associated with BMI in the region led to attenuation of this signal and uncovered another independent (r(2)<0.2), statistically significant association, rs186019316 (P=2.11×10(-4)). Both rs186019316 and rs7596758 or proxies are located in transcription factor binding regions. No significant association with rare variants was found in either the exons of TMEM18 or the 3' genome-wide association study region. CONCLUSIONS: Targeted sequencing around TMEM18 identified 2 novel BMI variants with possible regulatory function.
Keywords: Adult; Aged; Aging; Body Mass Index; Cohort Studies; Female; Genetic Association Studies; Genetic Variation; Genome-Wide Association Study; Genomics; Heart Diseases; Humans; Male; Membrane Proteins; Middle Aged; Polymorphism, Single Nucleotide; Sequence Analysis, DNA; Young Adult

Sequencing of 2 subclinical atherosclerosis candidate regions in 3669 individuals: Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) Consortium Targeted Sequencing Study. - Bis, Joshua C; White, Charles C; Franceschini, Nora; Brody, Jennifer; Zhang, Xiaoling; Muzny, Donna; Santibanez, Jireh; Gibbs, Richard; Liu, Xiaoming; Lin, Honghuang; Boerwinkle, Eric; Psaty, Bruce M; et al. (Circ Cardiovasc Genet, 2014)
BACKGROUND: Atherosclerosis, the precursor to coronary heart disease and stroke, is characterized by an accumulation of fatty cells in the arterial intimal-medial layers. Common carotid intima media thickness (cIMT) and plaque are subclinical atherosclerosis measures that predict cardiovascular disease events. Previously, genome-wide association studies demonstrated evidence for association with cIMT (SLC17A4) and plaque (PIK3CG). METHODS AND RESULTS: We sequenced 120 kb around SLC17A4 (6p22.2) and 251 kb around PIK3CG (7q22.3) among 3669 European ancestry participants from the Atherosclerosis Risk in Communities (ARIC) study, Cardiovascular Health Study (CHS), and Framingham Heart Study (FHS) in Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) Consortium. Primary analyses focused on 438 common variants (minor allele frequency ≥1%), which were independently meta-analyzed. A 3' untranslated region CCDC71L variant (rs2286149), upstream from PIK3CG, was the most significant finding in cIMT (P=0.00033) and plaque (P=0.0004) analyses. A SLC17A4 intronic variant was also associated with cIMT (P=0.008). Both were in low linkage disequilibrium with the genome-wide association study single nucleotide polymorphisms. Gene-based tests including T1 count and sequence kernel association test for rare variants (minor allele frequency <1%) did not yield statistically significant associations. However, we observed nominal associations for rare variants in CCDC71L and SLC17A3 with cIMT and of the entire 7q22 region with plaque (P=0.05). CONCLUSIONS: Common and rare variants in PIK3CG and SLC17A4 regions demonstrated modest association with subclinical atherosclerosis traits. Although not conclusive, these findings may help to understand the genetic architecture of regions previously implicated by genome-wide association studies and identify variants within these regions for further investigation in larger samples.
Keywords: Aged; Aged, 80 and over; Aging; Atherosclerosis; Class Ib Phosphatidylinositol 3-Kinase; Cohort Studies; European Continental Ancestry Group; Female; Genetic Variation; Genome-Wide Association Study; Genomics; Humans; Male; Middle Aged; Polymorphism, Single Nucleotide; Sequence Analysis, DNA; Sodium-Phosphate Cotransporter Proteins, Type I

Serum carboxymethyl-lysine, disability, and frailty in older persons: the Cardiovascular Health Study. - Whitson, Heather E; Arnold, Alice M; Yee, Laura M; Mukamal, Kenneth J; Kizer, Jorge R; Djoussé, Luc; Ix, Joachim H; Siscovick, David; Tracy, Russell P; Thielke, Stephen M; Hirsch, Calvin; Newman, Anne B; et al. (J Gerontol A Biol Sci Med Sci, 2014)
BACKGROUND: Advanced glycation endproducts are biologically active compounds that accumulate in disordered metabolism and normal aging. Carboxymethyl-lysine (CML), a ubiquitous human advanced glycation endproduct, has been associated with age-related conditions and mortality. Our objective was to ascertain the relationship between CML and geriatric outcomes (disability and frailty) in a large cohort of older men and women. METHODS: In 1996-1997, serum CML was measured in 3,373 Cardiovascular Health Study participants (mean age 78.1 ± 4.8 years). Disability, defined as difficulty in any of six activities of daily living, was assessed every 6-12 months for 14 years. Frailty was defined according to five standard criteria at the 1996-1997 visit. Cox proportional hazard models estimated the relationship between CML and incident disability (N = 2,643). Logistic regression models estimated the relationship between CML and prevalent frailty. RESULTS: Adjusting for multiple potential confounders, higher CML was associated with incident disability (hazard ratio per standard deviation [225 ng/mL] increase: 1.05, 95% CI 1.01-1.11). In men, odds of frailty increased with higher CML values (odds ratio = 1.30 per standard deviation, 95% CI 1.14-1.48), but the relationship was attenuated by adjustment for cognitive status, kidney function, and arthritis. CML was not associated with frailty in women. CONCLUSIONS: Higher serum CML levels in late life are associated with incident disability and prevalent frailty. Further work is needed to understand CML's value as a risk stratifier, biomarker, or target for interventions that promote healthy aging.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Aging; Biomarkers; Cardiac Rehabilitation; Cardiovascular Diseases; Disabled Persons; Female; Follow-Up Studies; Frail Elderly; Health Status; Humans; Incidence; Lysine; Male; Prevalence; Prognosis; Retrospective Studies; United States

Shared genetic susceptibility to ischemic stroke and coronary artery disease: a genome-wide analysis of common variants. - Dichgans, Martin; Malik, Rainer; König, Inke R; Rosand, Jonathan; Clarke, Robert; Gretarsdottir, Solveig; Thorleifsson, Gudmar; Mitchell, Braxton D; Assimes, Themistocles L; Levi, Christopher; O'Donnell, Christopher J; Fornage, Myriam; et al. (Stroke, 2014)
BACKGROUND AND PURPOSE: Ischemic stroke (IS) and coronary artery disease (CAD) share several risk factors and each has a substantial heritability. We conducted a genome-wide analysis to evaluate the extent of shared genetic determination of the two diseases. METHODS: Genome-wide association data were obtained from the METASTROKE, Coronary Artery Disease Genome-wide Replication and Meta-analysis (CARDIoGRAM), and Coronary Artery Disease (C4D) Genetics consortia. We first analyzed common variants reaching a nominal threshold of significance (P<0.01) for CAD for their association with IS and vice versa. We then examined specific overlap across phenotypes for variants that reached a high threshold of significance. Finally, we conducted a joint meta-analysis on the combined phenotype of IS or CAD. Corresponding analyses were performed restricted to the 2167 individuals with the ischemic large artery stroke (LAS) subtype. RESULTS: Common variants associated with CAD at P<0.01 were associated with a significant excess risk for IS and for LAS and vice versa. Among the 42 known genome-wide significant loci for CAD, 3 and 5 loci were significantly associated with IS and LAS, respectively. In the joint meta-analyses, 15 loci passed genome-wide significance (P<5×10(-8)) for the combined phenotype of IS or CAD and 17 loci passed genome-wide significance for LAS or CAD. Because these loci had prior evidence for genome-wide significance for CAD, we specifically analyzed the respective signals for IS and LAS and found evidence for association at chr12q24/SH2B3 (PIS=1.62×10(-7)) and ABO (PIS=2.6×10(-4)), as well as at HDAC9 (PLAS=2.32×10(-12)), 9p21 (PLAS=3.70×10(-6)), RAI1-PEMT-RASD1 (PLAS=2.69×10(-5)), EDNRA (PLAS=7.29×10(-4)), and CYP17A1-CNNM2-NT5C2 (PLAS=4.9×10(-4)). CONCLUSIONS: Our results demonstrate substantial overlap in the genetic risk of IS and particularly the LAS subtype with CAD.
Keywords: Brain Ischemia; Coronary Artery Disease; Data Interpretation, Statistical; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Phenotype; Polymorphism, Single Nucleotide; Reproducibility of Results; Risk Factors; Stroke

Simple biologically informed inflammatory index of two serum cytokines predicts 10 year all-cause mortality in older adults. - Varadhan, Ravi; Yao, Wenliang; Matteini, Amy; Beamer, Brock A; Xue, Qian-Li; Yang, Huanle; Manwani, Bhavish; Reiner, Alexander; Jenny, Nancy; Parekh, Neel; Fallin, M Daniele; Newman, Anne; et al. (J Gerontol A Biol Sci Med Sci, 2014)
BACKGROUND: Individual measurements of inflammation have been utilized to assess adverse outcomes risk in older adults with varying degrees of success. This study was designed to identify biologically informed, aggregate measures of inflammation for optimal risk assessment and to inform further biological study of inflammatory pathways. METHODS: In total, 15 nuclear factor-kappa B-mediated pathway markers of inflammation were first measured in baseline serum samples of 1,155 older participants in the InCHIANTI population. Of these, C-reactive protein, interleukin-1-receptor antagonist, interleukin-6, interleukin-18, and soluble tumor necrosis factor-α receptor-1 were independent predictors of 5-year mortality. These five inflammatory markers were measured in baseline serum samples of 5,600 Cardiovascular Health Study participants. A weighted summary score, the first principal component summary score, and an inflammation index score were developed from these five log-transformed inflammatory markers, and their prediction of 10-year all-cause mortality was evaluated in Cardiovascular Health Study and then validated in InCHIANTI. RESULTS: The inflammation index score that included interleukin-6 and soluble tumor necrosis factor-α receptor-1 was the best predictor of 10-year all-cause mortality in Cardiovascular Health Study, after adjusting for age, sex, education, race, smoking, and body mass index (hazards ratio = 1.62; 95% CI: 1.54, 1.70) compared with all other single and combined measures. The inflammation index score was also the best predictor of mortality in the InCHIANTI validation study (hazards ratio 1.33; 95% CI: 1.17-1.52). Stratification by sex and CVD status further strengthened the association of inflammation index score with mortality. CONCLUSION: A simple additive index of serum interleukin-6 and soluble tumor necrosis factor-α receptor-1 best captures the effect of chronic inflammation on mortality in older adults among the 15 biomarkers measured.
Keywords: Aged; Aged, 80 and over; Biomarkers; C-Reactive Protein; Cohort Studies; Female; Humans; Inflammation; Interleukin 1 Receptor Antagonist Protein; Interleukin-18; Interleukin-6; Longevity; Male; Receptors, Tumor Necrosis Factor, Type I; Risk Factors

Strategies to design and analyze targeted sequencing data: cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) Consortium Targeted Sequencing Study. - Lin, Honghuang; Wang, Min; Brody, Jennifer A; Bis, Joshua C; Dupuis, Josée; Lumley, Thomas; McKnight, Barbara; Rice, Kenneth M; Sitlani, Colleen M; Reid, Jeffrey G; Bressler, Jan; Liu, Xiaoming; et al. (Circ Cardiovasc Genet, 2014)
BACKGROUND: Genome-wide association studies have identified thousands of genetic variants that influence a variety of diseases and health-related quantitative traits. However, the causal variants underlying the majority of genetic associations remain unknown. Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) Consortium Targeted Sequencing Study aims to follow up genome-wide association study signals and identify novel associations of the allelic spectrum of identified variants with cardiovascular-related traits. METHODS AND RESULTS: The study included 4231 participants from 3 CHARGE cohorts: the Atherosclerosis Risk in Communities Study, the Cardiovascular Health Study, and the Framingham Heart Study. We used a case-cohort design in which we selected both a random sample of participants and participants with extreme phenotypes for each of 14 traits. We sequenced and analyzed 77 genomic loci, which had previously been associated with ≥1 of 14 phenotypes. A total of 52 736 variants were characterized by sequencing and passed our stringent quality control criteria. For common variants (minor allele frequency ≥1%), we performed unweighted regression analyses to obtain P values for associations and weighted regression analyses to obtain effect estimates that accounted for the sampling design. For rare variants, we applied 2 approaches: collapsed aggregate statistics and joint analysis of variants using the sequence kernel association test. CONCLUSIONS: We sequenced 77 genomic loci in participants from 3 cohorts. We established a set of filters to identify high-quality variants and implemented statistical and bioinformatics strategies to analyze the sequence data and identify potentially functional variants within genome-wide association study loci.
Keywords: Adult; Aged; Aged, 80 and over; Aging; Cohort Studies; Female; Genetic Variation; Genome-Wide Association Study; Genomics; Heart Diseases; Humans; Male; Middle Aged; Polymorphism, Single Nucleotide; Research Design; Sequence Analysis, DNA

Thyroid antibody status, subclinical hypothyroidism, and the risk of coronary heart disease: an individual participant data analysis. - Collet, Tinh-Hai; Bauer, Douglas C; Cappola, Anne R; Asvold, Bjørn O; Weiler, Stefan; Vittinghoff, Eric; Gussekloo, Jacobijn; Bremner, Alexandra; den Elzen, Wendy P J; Maciel, Rui M B; Vanderpump, Mark P J; Cornuz, Jacques; et al. (J Clin Endocrinol Metab, 2014)
CONTEXT: Subclinical hypothyroidism has been associated with increased risk of coronary heart disease (CHD), particularly with thyrotropin levels of 10.0 mIU/L or greater. The measurement of thyroid antibodies helps predict the progression to overt hypothyroidism, but it is unclear whether thyroid autoimmunity independently affects CHD risk. OBJECTIVE: The objective of the study was to compare the CHD risk of subclinical hypothyroidism with and without thyroid peroxidase antibodies (TPOAbs). DATA SOURCES AND STUDY SELECTION: A MEDLINE and EMBASE search from 1950 to 2011 was conducted for prospective cohorts, reporting baseline thyroid function, antibodies, and CHD outcomes. DATA EXTRACTION: Individual data of 38 274 participants from six cohorts for CHD mortality followed up for 460 333 person-years and 33 394 participants from four cohorts for CHD events. DATA SYNTHESIS: Among 38 274 adults (median age 55 y, 63% women), 1691 (4.4%) had subclinical hypothyroidism, of whom 775 (45.8%) had positive TPOAbs. During follow-up, 1436 participants died of CHD and 3285 had CHD events. Compared with euthyroid individuals, age- and gender-adjusted risks of CHD mortality in subclinical hypothyroidism were similar among individuals with and without TPOAbs [hazard ratio (HR) 1.15, 95% confidence interval (CI) 0.87-1.53 vs HR 1.26, CI 1.01-1.58, P for interaction = .62], as were risks of CHD events (HR 1.16, CI 0.87-1.56 vs HR 1.26, CI 1.02-1.56, P for interaction = .65). Risks of CHD mortality and events increased with higher thyrotropin, but within each stratum, risks did not differ by TPOAb status. CONCLUSIONS: CHD risk associated with subclinical hypothyroidism did not differ by TPOAb status, suggesting that biomarkers of thyroid autoimmunity do not add independent prognostic information for CHD outcomes.
Keywords: Adult; Aged; Aged, 80 and over; Autoantibodies; Coronary Disease; Female; Humans; Hypothyroidism; Incidence; Male; Middle Aged; Prevalence; Prognosis; Risk Factors; Seroepidemiologic Studies; Severity of Illness Index; Young Adult

Trans-ethnic meta-analysis of white blood cell phenotypes. - Keller, Margaux F; Reiner, Alexander P; Okada, Yukinori; van Rooij, Frank J A; Johnson, Andrew D; Chen, Ming-Huei; Smith, Albert V; Morris, Andrew P; Tanaka, Toshiko; Ferrucci, Luigi; Zonderman, Alan B; Lettre, Guillaume; et al. (Hum Mol Genet, 2014)
White blood cell (WBC) count is a common clinical measure used as a predictor of certain aspects of human health, including immunity and infection status. WBC count is also a complex trait that varies among individuals and ancestry groups. Differences in linkage disequilibrium structure and heterogeneity in allelic effects are expected to play a role in the associations observed between populations. Prior genome-wide association study (GWAS) meta-analyses have identified genomic loci associated with WBC and its subtypes, but much of the heritability of these phenotypes remains unexplained. Using GWAS summary statistics for over 50 000 individuals from three diverse populations (Japanese, African-American and European ancestry), a Bayesian model methodology was employed to account for heterogeneity between ancestry groups. This approach was used to perform a trans-ethnic meta-analysis of total WBC, neutrophil and monocyte counts. Ten previously known associations were replicated and six new loci were identified, including several regions harboring genes related to inflammation and immune cell function. Ninety-five percent credible interval regions were calculated to narrow the association signals and fine-map the putatively causal variants within loci. Finally, a conditional analysis was performed on the most significant SNPs identified by the trans-ethnic meta-analysis (MA), and nine secondary signals within loci previously associated with WBC or its subtypes were identified. This work illustrates the potential of trans-ethnic analysis and ascribes a critical role to multi-ethnic cohorts and consortia in exploring complex phenotypes with respect to variants that lie outside the European-biased GWAS pool.
Keywords: African Americans; Asian Continental Ancestry Group; Bayes Theorem; European Continental Ancestry Group; Genome, Human; Genome-Wide Association Study; Genotype; Humans; Leukocyte Count; Leukocytes; Linkage Disequilibrium; Phenotype; Polymorphism, Single Nucleotide; Quantitative Trait Loci

A variant of sparse partial least squares for variable selection and data exploration. - Olson Hunt, Megan J; Weissfeld, Lisa; Boudreau, Robert M; Aizenstein, Howard; Newman, Anne B; Simonsick, Eleanor M; Van Domelen, Dane R; Thomas, Fridtjof; Yaffe, Kristine; Rosano, Caterina (Front Neuroinform, 2014)
When data are sparse and/or predictors multicollinear, current implementation of sparse partial least squares (SPLS) does not give estimates for non-selected predictors nor provide a measure of inference. In response, an approach termed "all-possible" SPLS is proposed, which fits a SPLS model for all tuning parameter values across a set grid. Noted is the percentage of time a given predictor is chosen, as well as the average non-zero parameter estimate. Using a "large" number of multicollinear predictors, simulation confirmed variables not associated with the outcome were least likely to be chosen as sparsity increased across the grid of tuning parameters, while the opposite was true for those strongly associated. Lastly, variables with a weak association were chosen more often than those with no association, but less often than those with a strong relationship to the outcome. Similarly, predictors most strongly related to the outcome had the largest average parameter estimate magnitude, followed by those with a weak relationship, followed by those with no relationship. Across two independent studies regarding the relationship between volumetric MRI measures and a cognitive test score, this method confirmed a priori hypotheses about which brain regions would be selected most often and have the largest average parameter estimates. In conclusion, the percentage of time a predictor is chosen is a useful measure for ordering the strength of the relationship between the independent and dependent variables, serving as a form of inference. The average parameter estimates give further insight regarding the direction and strength of association. As a result, all-possible SPLS gives more information than the dichotomous output of traditional SPLS, making it useful when undertaking data exploration and hypothesis generation for a large number of potential predictors.

What do carotid intima-media thickness and plaque add to the prediction of stroke and cardiovascular disease risk in older adults? The cardiovascular health study. - Gardin, Julius M; Bartz, Traci M; Polak, Joseph F; O'Leary, Daniel H; Wong, Nathan D (J Am Soc Echocardiogr, 2014)
BACKGROUND: The aim of this study was to evaluate whether the addition of ultrasound carotid intima-media thickness (CIMT) measurements and risk categories of plaque help predict incident stroke and cardiovascular disease (CVD) in older adults. METHODS: Carotid ultrasound studies were recorded in the multicenter Cardiovascular Health Study. CVD was defined as coronary heart disease plus heart failure plus stroke. Ten-year risk prediction Cox proportional-hazards models for stroke and CVD were calculated using Cardiovascular Health Study-specific coefficients for Framingham risk score factors. Categories of CIMT and CIMT plus plaque were added to Framingham risk score prediction models, and categorical net reclassification improvement (NRI) and Harrell's c-statistic were calculated. RESULTS: In 4,384 Cardiovascular Health Study participants (61% women, 14% black; mean baseline age, 72 ± 5 years) without CVD at baseline, higher CIMT category and the presence of plaque were both associated with higher incidence rates for stroke and CVD. The addition of CIMT improved the ability of Framingham risk score-type risk models to discriminate cases from noncases of incident stroke and CVD (NRI = 0.062, P = .015, and NRI = 0.027, P < .001, respectively), with no further improvement by adding plaque. For both outcomes, NRI was driven by down-classifying those without incident disease. Although the addition of plaque to CIMT did not result in a significant NRI for either outcome, it was significant among those without incident disease. CONCLUSIONS: In older adults, the addition of CIMT modestly improves 10-year risk prediction for stroke and CVD beyond a traditional risk factor model, mainly by down-classifying risk in those without stroke or CVD; the addition of plaque to CIMT adds no statistical benefit in the overall cohort, although there is evidence of down-classification in those without events.
Keywords: Aged; Cardiovascular Diseases; Carotid Intima-Media Thickness; Carotid Stenosis; Comorbidity; Female; Humans; Incidence; Longitudinal Studies; Male; Reproducibility of Results; Risk Factors; Sensitivity and Specificity; Stroke; Survival Rate

Whole-exome sequencing identifies rare and low-frequency coding variants associated with LDL cholesterol. - Lange, Leslie A; Hu, Youna; Zhang, He; Xue, Chenyi; Schmidt, Ellen M; Tang, Zheng-Zheng; Bizon, Chris; Lange, Ethan M; Smith, Joshua D; Turner, Emily H; Jun, Goo; Kang, Hyun Min; et al. (Am J Hum Genet, 2014)
Elevated low-density lipoprotein cholesterol (LDL-C) is a treatable, heritable risk factor for cardiovascular disease. Genome-wide association studies (GWASs) have identified 157 variants associated with lipid levels but are not well suited to assess the impact of rare and low-frequency variants. To determine whether rare or low-frequency coding variants are associated with LDL-C, we exome sequenced 2,005 individuals, including 554 individuals selected for extreme LDL-C (>98(th) or <2(nd) percentile). Follow-up analyses included sequencing of 1,302 additional individuals and genotype-based analysis of 52,221 individuals. We observed significant evidence of association between LDL-C and the burden of rare or low-frequency variants in PNPLA5, encoding a phospholipase-domain-containing protein, and both known and previously unidentified variants in PCSK9, LDLR and APOB, three known lipid-related genes. The effect sizes for the burden of rare variants for each associated gene were substantially higher than those observed for individual SNPs identified from GWASs. We replicated the PNPLA5 signal in an independent large-scale sequencing study of 2,084 individuals. In conclusion, this large whole-exome-sequencing study for LDL-C identified a gene not known to be implicated in LDL-C and provides unique insight into the design and analysis of similar experiments.
Keywords: Adult; Aged; Apolipoproteins E; Cholesterol, LDL; Cohort Studies; Dyslipidemias; Exome; Female; Follow-Up Studies; Gene Frequency; Genetic Code; Genome-Wide Association Study; Genotype; Humans; Lipase; Male; Middle Aged; Phenotype; Polymorphism, Single Nucleotide; Proprotein Convertase 9; Proprotein Convertases; Receptors, LDL; Sequence Analysis, DNA; Serine Endopeptidases

Association between hospitalization for pneumonia and subsequent risk of cardiovascular disease. - Corrales-Medina, Vicente F; Alvarez, Karina N; Weissfeld, Lisa A; Angus, Derek C; Chirinos, Julio A; Chang, Chung-Chou H; Newman, Anne; Loehr, Laura; Folsom, Aaron R; Elkind, Mitchell S; Lyles, Mary F; Kronmal, Richard A; et al. (JAMA, 2015)
IMPORTANCE: The risk of cardiovascular disease (CVD) after infection is poorly understood. OBJECTIVE: To determine whether hospitalization for pneumonia is associated with an increased short-term and long-term risk of CVD. DESIGN, SETTINGS, AND PARTICIPANTS: We examined 2 community-based cohorts: the Cardiovascular Health Study (CHS, n = 5888; enrollment age, ≥65 years; enrollment period, 1989-1994) and the Atherosclerosis Risk in Communities study (ARIC, n = 15,792; enrollment age, 45-64 years; enrollment period, 1987-1989). Participants were followed up through December 31, 2010. We matched each participant hospitalized with pneumonia to 2 controls. Pneumonia cases and controls were followed for occurrence of CVD over 10 years after matching. We estimated hazard ratios (HRs) for CVD at different time intervals, adjusting for demographics, CVD risk factors, subclinical CVD, comorbidities, and functional status. EXPOSURES: Hospitalization for pneumonia. MAIN OUTCOMES AND MEASURES: Incident CVD (myocardial infarction, stroke, and fatal coronary heart disease). RESULTS: Of 591 pneumonia cases in CHS, 206 had CVD events over 10 years after pneumonia hospitalization. CVD risk after pneumonia was highest in the first year. CVD occurred in 54 cases and 6 controls in the first 30 days (HR, 4.07; 95% CI, 2.86-5.27); 11 cases and 9 controls between 31 and 90 days (HR, 2.94; 95% CI, 2.18-3.70); and 22 cases and 55 controls between 91 days and 1 year (HR, 2.10; 95% CI, 1.59-2.60). Additional CVD risk remained elevated into the tenth year, when 4 cases and 12 controls developed CVD (HR, 1.86; 95% CI, 1.18-2.55). In ARIC, of 680 pneumonia cases, 112 had CVD over 10 years after hospitalization. CVD occurred in 4 cases and 3 controls in the first 30 days (HR, 2.38; 95% CI, 1.12-3.63); 4 cases and 0 controls between 31 and 90 days (HR, 2.40; 95% CI, 1.23-3.47); 11 cases and 8 controls between 91 days and 1 year (HR, 2.19; 95% CI, 1.20-3.19); and 8 cases and 7 controls during the second year (HR, 1.88; 95% CI, 1.10-2.66). After the second year, the HRs were no longer statistically significant. CONCLUSIONS AND RELEVANCE: Hospitalization for pneumonia was associated with increased short-term and long-term risk of CVD, suggesting that pneumonia may be a risk factor for CVD.
Keywords: Aged; Atherosclerosis; Cardiovascular Diseases; Cohort Studies; Comorbidity; Female; Hospitalization; Humans; Male; Middle Aged; Pneumonia; Risk Factors

Association of Alzheimer's disease GWAS loci with MRI markers of brain aging. - Chauhan, Ganesh; Adams, Hieab H H; Bis, Joshua C; Weinstein, Galit; Yu, Lei; Töglhofer, Anna Maria; Smith, Albert Vernon; van der Lee, Sven J; Gottesman, Rebecca F; Thomson, Russell; Wang, Jing; Yang, Qiong; et al. (Neurobiol Aging, 2015)
Whether novel risk variants of Alzheimer's disease (AD) identified through genome-wide association studies also influence magnetic resonance imaging-based intermediate phenotypes of AD in the general population is unclear. We studied association of 24 AD risk loci with intracranial volume, total brain volume, hippocampal volume (HV), white matter hyperintensity burden, and brain infarcts in a meta-analysis of genetic association studies from large population-based samples (N = 8175-11,550). In single-SNP based tests, AD risk allele of APOE (rs2075650) was associated with smaller HV (p = 0.0054) and CD33 (rs3865444) with smaller intracranial volume (p = 0.0058). In gene-based tests, there was associations of HLA-DRB1 with total brain volume (p = 0.0006) and BIN1 with HV (p = 0.00089). A weighted AD genetic risk score was associated with smaller HV (beta ± SE = -0.047 ± 0.013, p = 0.00041), even after excluding the APOE locus (p = 0.029). However, only association of AD genetic risk score with HV, including APOE, was significant after multiple testing correction (including number of independent phenotypes tested). These results suggest that novel AD genetic risk variants may contribute to structural brain aging in nondemented older community persons.
Keywords: Aging; Alleles; Alzheimer Disease; Apolipoproteins E; Brain; Female; Genome-Wide Association Study; Hippocampus; Humans; Magnetic Resonance Imaging; Male; Organ Size; Polymorphism, Single Nucleotide; Risk; Sialic Acid Binding Ig-like Lectin 3

Association of Cardiometabolic Multimorbidity With Mortality. - Di Angelantonio, Emanuele; Kaptoge, Stephen; Wormser, David; Willeit, Peter; Butterworth, Adam S; Bansal, Narinder; O'Keeffe, Linda M; Gao, Pei; Wood, Angela M; Burgess, Stephen; Freitag, Daniel F; Pennells, Lisa; et al. (JAMA, 2015)
IMPORTANCE: The prevalence of cardiometabolic multimorbidity is increasing. OBJECTIVE: To estimate reductions in life expectancy associated with cardiometabolic multimorbidity. DESIGN, SETTING, AND PARTICIPANTS: Age- and sex-adjusted mortality rates and hazard ratios (HRs) were calculated using individual participant data from the Emerging Risk Factors Collaboration (689,300 participants; 91 cohorts; years of baseline surveys: 1960-2007; latest mortality follow-up: April 2013; 128,843 deaths). The HRs from the Emerging Risk Factors Collaboration were compared with those from the UK Biobank (499,808 participants; years of baseline surveys: 2006-2010; latest mortality follow-up: November 2013; 7995 deaths). Cumulative survival was estimated by applying calculated age-specific HRs for mortality to contemporary US age-specific death rates. EXPOSURES: A history of 2 or more of the following: diabetes mellitus, stroke, myocardial infarction (MI). MAIN OUTCOMES AND MEASURES: All-cause mortality and estimated reductions in life expectancy. RESULTS: In participants in the Emerging Risk Factors Collaboration without a history of diabetes, stroke, or MI at baseline (reference group), the all-cause mortality rate adjusted to the age of 60 years was 6.8 per 1000 person-years. Mortality rates per 1000 person-years were 15.6 in participants with a history of diabetes, 16.1 in those with stroke, 16.8 in those with MI, 32.0 in those with both diabetes and MI, 32.5 in those with both diabetes and stroke, 32.8 in those with both stroke and MI, and 59.5 in those with diabetes, stroke, and MI. Compared with the reference group, the HRs for all-cause mortality were 1.9 (95% CI, 1.8-2.0) in participants with a history of diabetes, 2.1 (95% CI, 2.0-2.2) in those with stroke, 2.0 (95% CI, 1.9-2.2) in those with MI, 3.7 (95% CI, 3.3-4.1) in those with both diabetes and MI, 3.8 (95% CI, 3.5-4.2) in those with both diabetes and stroke, 3.5 (95% CI, 3.1-4.0) in those with both stroke and MI, and 6.9 (95% CI, 5.7-8.3) in those with diabetes, stroke, and MI. The HRs from the Emerging Risk Factors Collaboration were similar to those from the more recently recruited UK Biobank. The HRs were little changed after further adjustment for markers of established intermediate pathways (eg, levels of lipids and blood pressure) and lifestyle factors (eg, smoking, diet). At the age of 60 years, a history of any 2 of these conditions was associated with 12 years of reduced life expectancy and a history of all 3 of these conditions was associated with 15 years of reduced life expectancy. CONCLUSIONS AND RELEVANCE: Mortality associated with a history of diabetes, stroke, or MI was similar for each condition. Because any combination of these conditions was associated with multiplicative mortality risk, life expectancy was substantially lower in people with multimorbidity.
Keywords: Adult; Aged; Comorbidity; Diabetes Mellitus; Female; Humans; Life Expectancy; Male; Middle Aged; Mortality; Myocardial Infarction; Risk Factors; Stroke

Association of exome sequences with plasma C-reactive protein levels in >9000 participants. - Schick, Ursula M; Auer, Paul L; Bis, Joshua C; Lin, Honghuang; Wei, Peng; Pankratz, Nathan; Lange, Leslie A; Brody, Jennifer; Stitziel, Nathan O; Kim, Daniel S; Carlson, Christopher S; Fornage, Myriam; et al. (Hum Mol Genet, 2015)
C-reactive protein (CRP) concentration is a heritable systemic marker of inflammation that is associated with cardiovascular disease risk. Genome-wide association studies have identified CRP-associated common variants associated in ∼25 genes. Our aims were to apply exome sequencing to (1) assess whether the candidate loci contain rare coding variants associated with CRP levels and (2) perform an exome-wide search for rare variants in novel genes associated with CRP levels. We exome-sequenced 6050 European-Americans (EAs) and 3109 African-Americans (AAs) from the NHLBI-ESP and the CHARGE consortia, and performed association tests of sequence data with measured CRP levels. In single-variant tests across candidate loci, a novel rare (minor allele frequency = 0.16%) CRP-coding variant (rs77832441-A; p.Thr59Met) was associated with 53% lower mean CRP levels (P = 2.9 × 10(-6)). We replicated the association of rs77832441 in an exome array analysis of 11 414 EAs (P = 3.0 × 10(-15)). Despite a strong effect on CRP levels, rs77832441 was not associated with inflammation-related phenotypes including coronary heart disease. We also found evidence for an AA-specific association of APOE-ε2 rs7214 with higher CRP levels. At the exome-wide significance level (P < 5.0 × 10(-8)), we confirmed associations for reported common variants of HNF1A, CRP, IL6R and TOMM40-APOE. In gene-based tests, a burden of rare/lower frequency variation in CRP in EAs (P ≤ 6.8 × 10(-4)) and in retinoic acid receptor-related orphan receptor α (RORA) in AAs (P = 1.7 × 10(-3)) were associated with CRP levels at the candidate gene level (P < 2.0 × 10(-3)). This inquiry did not elucidate novel genes, but instead demonstrated that variants distributed across the allele frequency spectrum within candidate genes contribute to CRP levels.
Keywords: Adult; African Americans; C-Reactive Protein; Cardiovascular Diseases; Cohort Studies; European Continental Ancestry Group; Exome; Female; Gene Frequency; Genetic Predisposition to Disease; Genome-Wide Association Study; Hepatocyte Nuclear Factor 1-alpha; Humans; Male; Plasma; Polymorphism, Single Nucleotide; Receptors, Interleukin-6; Risk Factors

Association of mitochondrial DNA levels with frailty and all-cause mortality. - Ashar, Foram N; Moes, Anna; Moore, Ann Z; Grove, Megan L; Chaves, Paulo H M; Coresh, Josef; Newman, Anne B; Matteini, Amy M; Bandeen-Roche, Karen; Boerwinkle, Eric; Walston, Jeremy D; Arking, Dan E (J Mol Med (Berl), 2015)
Mitochondrial function is altered with age and variants in mitochondrial DNA (mtDNA) modulate risk for several age-related disease states. However, the association of mtDNA copy number, a readily available marker which reflects mitochondrial depletion, energy reserves, and oxidative stress, on aging and mortality in the general population has not been addressed. To assess the association between mtDNA copy number and two primary outcomes--prevalent frailty and all-cause mortality--we utilize data from participants who were from two multicenter, multiethnic, community-based, prospective studies--the Cardiovascular Health Study (CHS) (1989-2006) and the Atherosclerosis Risk in Communities (ARIC) study (1987-2013). A total of 4892 participants (43.3% men) from CHS and 11,509 participants (44.9% men) from ARIC self-identifying as white or black were included in the analysis. mtDNA copy number, the trait of interest, was measured using a qPCR-based method in CHS and an array-based method in ARIC from DNA isolated from whole blood in participants from both cohorts. In race-stratified meta-analyses, we observe a significant inverse association of mtDNA copy number with age and higher mtDNA copy number in women relative to men. Lower mtDNA copy number was also significantly associated with prevalent frailty in white participants from CHS (OR 0.91, 95% CI 0.85-0.97). Additionally, mtDNA copy number was a strong independent predictor of all-cause mortality in an age- and sex-adjusted, race-stratified analysis of 16,401 participants from both cohorts with a pooled hazard ratio of 1.47 (95% CI 1.33-1.62) for the lowest quintile of mtDNA copy number relative to the highest quintile. Key messages: Mitochondrial DNA (mtDNA) copy number is associated with age and sex. Lower mtDNA copy number is also associated with prevalent frailty. mtDNA copy number is a significant predictor of all-cause mortality in a multiethnic population.
Keywords: African Americans; Aged; Aged, 80 and over; Aging; DNA, Mitochondrial; European Continental Ancestry Group; Female; Follow-Up Studies; Gene Dosage; Geriatric Assessment; Humans; Kaplan-Meier Estimate; Male; Mortality; Odds Ratio; Population Surveillance; Prospective Studies; Surveys and Questionnaires; United States

Association of Rare Loss-Of-Function Alleles in HAL, Serum Histidine: Levels and Incident Coronary Heart Disease. - Yu, Bing; Li, Alexander H; Muzny, Donna; Veeraraghavan, Narayanan; de Vries, Paul S; Bis, Joshua C; Musani, Solomon K; Alexander, Danny; Morrison, Alanna C; Franco, Oscar H; Uitterlinden, Andre; Hofman, Albert; et al. (Circ Cardiovasc Genet, 2015)
BACKGROUND: Histidine is a semiessential amino acid with antioxidant and anti-inflammatory properties. Few data are available on the associations between genetic variants, histidine levels, and incident coronary heart disease (CHD) in a population-based sample. METHODS AND RESULTS: By conducting whole exome sequencing on 1152 African Americans in the Atherosclerosis Risk in Communities (ARIC) study and focusing on loss-of-function (LoF) variants, we identified 3 novel rare LoF variants in HAL, a gene that encodes histidine ammonia-lyase in the first step of histidine catabolism. These LoF variants had large effects on blood histidine levels (β=0.26; P=1.2×10(-13)). The positive association with histidine levels was replicated by genotyping an independent sample of 718 ARIC African Americans (minor allele frequency=1%; P=1.2×10(-4)). In addition, high blood histidine levels were associated with reduced risk of developing incident CHD with an average of 21.5 years of follow-up among African Americans (hazard ratio=0.18; P=1.9×10(-4)). This finding was validated in an independent sample of European Americans from the Framingham Heart Study (FHS) Offspring Cohort. However, LoF variants in HAL were not directly significantly associated with incident CHD after meta-analyzing results from the CHARGE Consortium. CONCLUSIONS: Three LoF mutations in HAL were associated with increased histidine levels, which in turn were shown to be inversely related to the risk of CHD among both African Americans and European Americans. Future investigations on the association between HAL gene variation and CHD are warranted.
Keywords: Adult; African Americans; Alleles; Coronary Disease; European Continental Ancestry Group; Female; Histidine; Histidine Ammonia-Lyase; Humans; Male; Mutation

Cardiovascular and Mortality Outcomes in the Elderly With Impaired Cardiac and Pulmonary Function: The Cardiovascular Health Study (CHS). - Waheed, Salman; Chaves, Paulo H M; Gardin, Julius M; Cao, Jie Jane (J Am Heart Assoc, 2015)
BACKGROUND: Impaired pulmonary function (IPF) and left ventricular systolic dysfunction (LVSD) are prevalent in the elderly and are associated with significant morbidity and mortality. The main objectives of this study were to examine the relative impact and joint association of IPF and LVSD with heart failure, cardiovascular mortality and all-cause mortality, and their impact on risk classification using a continuous net reclassification index. METHODS AND RESULTS: We followed 2342 adults without prevalent cardiovascular disease (mean age, 76 years) from the Cardiovascular Health Study for a median of 12.6 years. LVSD was defined as LV ejection fraction <55%. IPF was defined as: forced expiratory volume in 1 second:forced vital capacity <70%, and predicted forced expiratory volume in 1 second <80%. Outcomes included heart failure hospitalization, cardiovascular mortality, all-cause mortality, and composite outcome. LVSD was detected in 128 subjects (6%), IPF in 441 (19%) and both in 38 (2%). Compared to those without LVSD or IPF, there was a significantly increased cardiovascular risk for groups of LVSD only, IPF only, and LVSD plus IPF, adjusted hazard ratio (95% CI) 2.1 (1.5-3.0), 1.7 (1.4-2.1), and 3.2 (2.0-5.1) for HF; 1.8 (1.2-2.6), 1.4 (1.1-1.8), and 2.8 (1.7-4.7) for cardiovascular mortality; 1.3 (1.0-1.8), 1.7 (1.4-1.9), and 2.1 (1.5-3.0) for all-cause mortality, and 1.6 (1.3-2.1), 1.7 (1.5-1.9), and 2.4 (1.7-3.3) for composite outcome, respectively. Risk classification improved significantly for all outcomes when IPF was added to the adjusted model with LVSD or LVSD to IPF. CONCLUSIONS: While risk of cardiovascular outcomes was the highest among elderly with both LVSD and IPF, risk was comparable between subjects with IPF alone and those with LVSD alone. This observation, combined with improved risk classification by adding IPF to LVSD or LVSD to IPF, underscore the importance of comprehensive heart and lung evaluation in cardiovascular outcome assessment.
Keywords: Aged; Aged, 80 and over; Cardiovascular Diseases; Female; Heart Diseases; Heart Failure; Hospitalization; Humans; Kaplan-Meier Estimate; Lung Diseases; Male; Mortality; Prospective Studies; Respiratory Function Tests; Risk Assessment; Risk Factors; Stroke Volume; United States; Ventricular Dysfunction, Left

Circulating and dietary trans fatty acids and incident type 2 diabetes in older adults: the Cardiovascular Health Study. - Wang, Qianyi; Imamura, Fumiaki; Ma, Wenjie; Wang, Molin; Lemaitre, Rozenn N; King, Irena B; Song, Xiaoling; Biggs, Mary L; Delaney, Joseph A; Mukamal, Kenneth J; Djoussé, Luc; Siscovick, David S; et al. (Diabetes Care, 2015)
OBJECTIVE: To investigate the effects of trans fatty acids (TFAs) on type 2 diabetes mellitus (DM) by specific TFA subtype or method of assessment. RESEARCH DESIGN AND METHODS: In the Cardiovascular Health Study, plasma phospholipid trans (t)-16:1n9, t-18:1, and cis (c)/t-, t/c-, and t/t-18:2 were measured in blood drawn from 2,919 adults aged 74 ± 5 years and free of prevalent DM in 1992. Dietary TFA was estimated among 4,207 adults free of prevalent DM when dietary questionnaires were initially administered in 1989 or 1996. Incident DM was defined through 2010 by medication use or blood glucose levels. Risks were assessed by Cox proportional hazards. RESULTS: In biomarker analyses, 287 DM cases occurred during 30,825 person-years. Both t-16:1n9 (extreme quartile hazard ratio 1.59 [95% CI 1.04-2.42], P-trend = 0.04) and t-18:1 (1.91 [1.20-3.03], P-trend = 0.01) levels were associated with higher incident DM after adjustment for de novo lipogenesis fatty acids. In dietary analyses, 407 DM cases occurred during 50,105 person-years. Incident DM was positively associated with consumption of total TFAs (1.38 [1.03-1.86], P-trend = 0.02), t-18:1 (1.32 [1.00-1.76], P-trend = 0.04), and t-18:2 (1.41 [1.05-1.89], P-trend = 0.02). After further adjustment for other dietary habits, however, the associations of estimated dietary TFA with DM were attenuated, and only nonsignificant positive trends remained. CONCLUSIONS: Among older adults, plasma phospholipid t-16:1n9 and t-18:1 levels were positively related to DM after adjustment for de novo lipogenesis fatty acids. Estimated dietary TFA was not significantly associated with DM. These findings highlight the need for further observational, interventional, and experimental studies of the effects TFA on DM.
Keywords: Aged; Biomarkers; Diabetes Mellitus, Type 2; Diabetic Angiopathies; Dietary Fats, Unsaturated; Epidemiologic Methods; Female; Food Habits; Humans; Male; Phospholipids; Trans Fatty Acids

Coagulation factor XII genetic variation, ex vivo thrombin generation, and stroke risk in the elderly: results from the Cardiovascular Health Study. - Olson, N C; Butenas, S; Lange, L A; Lange, E M; Cushman, M; Jenny, N S; Walston, J; Souto, J C; Soria, J M; Chauhan, G; Debette, S; Longstreth, W T; et al. (J Thromb Haemost, 2015)
BACKGROUND: The relationships of thrombin generation (TG) with cardiovascular disease risk are underevaluated in population-based cohorts. OBJECTIVES: To evaluate the relationships of TG influenced by the contact and tissue factor coagulation pathways ex vivo with common single-nucleotide polymorphisms (SNPs) and incident cardiovascular disease and stroke. PATIENTS/METHODS: We measured peak TG (pTG) in baseline plasma samples of Cardiovascular Health Study participants (n = 5411), both with and without inhibitory anti-factor XIa antibody (pTG/FXIa(-) ). We evaluated their associations with ~ 50 000 SNPs by using the IBCv2 genotyping array, and with incident cardiovascular disease and stroke events over a median follow-up of 13.2 years. RESULTS: The minor allele for an SNP in the FXII gene (F12), rs1801020, was associated with lower pTG in European-Americans (β = - 34.2 ± 3.5 nm; P = 3.3 × 10(-22) ; minor allele frequency [MAF] = 0.23) and African-Americans (β = - 31.1 ± 7.9 nm; P = 9.0 × 10(-5) ; MAF = 0.42). Lower FXIa-independent pTG (pTG/FXIa(-) ) was associated with the F12 rs1801020 minor allele, and higher pTG/FXIa(-) was associated with the ABO SNP rs657152 minor allele (β = 16.3 nm; P = 4.3 × 10(-9) ; MAF = 0.37). The risk factor-adjusted ischemic stroke hazard ratios were 1.09 (95% confidence interval CI 1.01-1.17; P = 0.03) for pTG, 1.06 (95% CI 0.98-1.15; P = 0.17) for pTG/FXIa(-) , and 1.11 (95% CI 1.02-1.21; P = 0.02) for FXIa-dependent pTG (pTG/FXIa(+) ), per one standard deviation increment (n = 834 ischemic strokes). In a multicohort candidate gene analysis, rs1801020 was not associated with incident ischemic stroke (β = - 0.02; standard error = 0.08; P = 0.81). CONCLUSIONS: These results support the importance of contact activation pathway-dependent TG as a risk factor for ischemic stroke, and indicate the importance of F12 SNPs for TG ex vivo and in vivo.
Keywords: African Americans; Age Factors; Aged; Blood Coagulation; Brain Ischemia; European Continental Ancestry Group; Factor XII; Female; Gene Frequency; Genetic Predisposition to Disease; Humans; Incidence; Male; Phenotype; Polymorphism, Single Nucleotide; Prospective Studies; Risk Assessment; Risk Factors; Stroke; Thrombin; Time Factors; United States

Common variation in COL4A1/COL4A2 is associated with sporadic cerebral small vessel disease. - Rannikmae, Kristiina; Davies, Gail; Thomson, Pippa A; Bevan, Steve; Devan, William J; Falcone, Guido J; Traylor, Matthew; Anderson, Christopher D; Battey, Thomas W K; Radmanesh, Farid; Deka, Ranjan; Woo, Jessica G; et al. (Neurology, 2015)
OBJECTIVES: We hypothesized that common variants in the collagen genes COL4A1/COL4A2 are associated with sporadic forms of cerebral small vessel disease. METHODS: We conducted meta-analyses of existing genotype data among individuals of European ancestry to determine associations of 1,070 common single nucleotide polymorphisms (SNPs) in the COL4A1/COL4A2 genomic region with the following: intracerebral hemorrhage and its subtypes (deep, lobar) (1,545 cases, 1,485 controls); ischemic stroke and its subtypes (cardioembolic, large vessel disease, lacunar) (12,389 cases, 62,004 controls); and white matter hyperintensities (2,733 individuals with ischemic stroke and 9,361 from population-based cohorts with brain MRI data). We calculated a statistical significance threshold that accounted for multiple testing and linkage disequilibrium between SNPs (p < 0.000084). RESULTS: Three intronic SNPs in COL4A2 were significantly associated with deep intracerebral hemorrhage (lead SNP odds ratio [OR] 1.29, 95% confidence interval [CI] 1.14-1.46, p = 0.00003; r(2) > 0.9 between SNPs). Although SNPs associated with deep intracerebral hemorrhage did not reach our significance threshold for association with lacunar ischemic stroke (lead SNP OR 1.10, 95% CI 1.03-1.18, p = 0.0073), and with white matter hyperintensity volume in symptomatic ischemic stroke patients (lead SNP OR 1.07, 95% CI 1.01-1.13, p = 0.016), the direction of association was the same. There was no convincing evidence of association with white matter hyperintensities in population-based studies or with non-small vessel disease cerebrovascular phenotypes. CONCLUSIONS: Our results indicate an association between common variation in the COL4A2 gene and symptomatic small vessel disease, particularly deep intracerebral hemorrhage. These findings merit replication studies, including in ethnic groups of non-European ancestry.
Keywords: Cerebral Small Vessel Diseases; Collagen Type IV; Genetic Association Studies; Genetic Variation; Humans; Polymorphism, Single Nucleotide

Consumption of meat is associated with higher fasting glucose and insulin concentrations regardless of glucose and insulin genetic risk scores: a meta-analysis of 50,345 Caucasians. - Fretts, Amanda M; Follis, Jack L; Nettleton, Jennifer A; Lemaitre, Rozenn N; Ngwa, Julius S; Wojczynski, Mary K; Kalafati, Ioanna Panagiota; Varga, Tibor V; Frazier-Wood, Alexis C; Houston, Denise K; Lahti, Jari; Ericson, Ulrika; et al. (Am J Clin Nutr, 2015)
BACKGROUND: Recent studies suggest that meat intake is associated with diabetes-related phenotypes. However, whether the associations of meat intake and glucose and insulin homeostasis are modified by genes related to glucose and insulin is unknown. OBJECTIVE: We investigated the associations of meat intake and the interaction of meat with genotype on fasting glucose and insulin concentrations in Caucasians free of diabetes mellitus. DESIGN: Fourteen studies that are part of the Cohorts for Heart and Aging Research in Genomic Epidemiology consortium participated in the analysis. Data were provided for up to 50,345 participants. Using linear regression within studies and a fixed-effects meta-analysis across studies, we examined 1) the associations of processed meat and unprocessed red meat intake with fasting glucose and insulin concentrations; and 2) the interactions of processed meat and unprocessed red meat with genetic risk score related to fasting glucose or insulin resistance on fasting glucose and insulin concentrations. RESULTS: Processed meat was associated with higher fasting glucose, and unprocessed red meat was associated with both higher fasting glucose and fasting insulin concentrations after adjustment for potential confounders [not including body mass index (BMI)]. For every additional 50-g serving of processed meat per day, fasting glucose was 0.021 mmol/L (95% CI: 0.011, 0.030 mmol/L) higher. Every additional 100-g serving of unprocessed red meat per day was associated with a 0.037-mmol/L (95% CI: 0.023, 0.051-mmol/L) higher fasting glucose concentration and a 0.049-ln-pmol/L (95% CI: 0.035, 0.063-ln-pmol/L) higher fasting insulin concentration. After additional adjustment for BMI, observed associations were attenuated and no longer statistically significant. The association of processed meat and fasting insulin did not reach statistical significance after correction for multiple comparisons. Observed associations were not modified by genetic loci known to influence fasting glucose or insulin resistance. CONCLUSION: The association of higher fasting glucose and insulin concentrations with meat consumption was not modified by an index of glucose- and insulin-related single-nucleotide polymorphisms. Six of the participating studies are registered at clinicaltrials.gov as NCT0000513 (Atherosclerosis Risk in Communities), NCT00149435 (Cardiovascular Health Study), NCT00005136 (Family Heart Study), NCT00005121 (Framingham Heart Study), NCT00083369 (Genetics of Lipid Lowering Drugs and Diet Network), and NCT00005487 (Multi-Ethnic Study of Atherosclerosis).
Keywords: Blood Glucose; Cohort Studies; Genetic Association Studies; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Hyperglycemia; Hyperinsulinism; Insulin; Insulin Resistance; Insulin-Secreting Cells; Meat; Meat Products; Middle Aged; Polymorphism, Single Nucleotide; Risk Factors

Dietary fatty acids modulate associations between genetic variants and circulating fatty acids in plasma and erythrocyte membranes: Meta-analysis of nine studies in the CHARGE consortium. - Smith, Caren E; Follis, Jack L; Nettleton, Jennifer A; Foy, Millennia; Wu, Jason H Y; Ma, Yiyi; Tanaka, Toshiko; Manichakul, Ani W; Wu, Hongyu; Chu, Audrey Y; Steffen, Lyn M; Fornage, Myriam; et al. (Mol Nutr Food Res, 2015)
SCOPE: Tissue concentrations of omega-3 fatty acids may reduce cardiovascular disease risk, and genetic variants are associated with circulating fatty acids concentrations. Whether dietary fatty acids interact with genetic variants to modify circulating omega-3 fatty acids is unclear. We evaluated interactions between genetic variants and fatty acid intakes for circulating alpha-linoleic acid, eicosapentaenoic acid, docosahexaenoic acid, and docosapentaenoic acid. METHODS AND RESULTS: We conducted meta-analyses (N = 11 668) evaluating interactions between dietary fatty acids and genetic variants (rs174538 and rs174548 in FADS1 (fatty acid desaturase 1), rs7435 in AGPAT3 (1-acyl-sn-glycerol-3-phosphate), rs4985167 in PDXDC1 (pyridoxal-dependent decarboxylase domain-containing 1), rs780094 in GCKR (glucokinase regulatory protein), and rs3734398 in ELOVL2 (fatty acid elongase 2)). Stratification by measurement compartment (plasma versus erthyrocyte) revealed compartment-specific interactions between FADS1 rs174538 and rs174548 and dietary alpha-linolenic acid and linoleic acid for docosahexaenoic acid and docosapentaenoic acid. CONCLUSION: Our findings reinforce earlier reports that genetically based differences in circulating fatty acids may be partially due to differences in the conversion of fatty acid precursors. Further, fatty acids measurement compartment may modify gene-diet relationships, and considering compartment may improve the detection of gene-fatty acids interactions for circulating fatty acid outcomes.
Keywords: Acetyltransferases; Acyltransferases; Adaptor Proteins, Signal Transducing; Carboxy-Lyases; Diet; Docosahexaenoic Acids; Eicosapentaenoic Acid; Erythrocyte Membrane; Fatty Acid Desaturases; Fatty Acids; Fatty Acids, Omega-3; Female; Humans; Male; Middle Aged; Polymorphism, Single Nucleotide

Drug-Gene Interactions of Antihypertensive Medications and Risk of Incident Cardiovascular Disease: A Pharmacogenomics Study from the CHARGE Consortium. - Bis, Joshua C; Sitlani, Colleen; Irvin, Ryan; Avery, Christy L; Smith, Albert Vernon; Sun, Fangui; Evans, Daniel S; Musani, Solomon K; Li, Xiaohui; Trompet, Stella; Krijthe, Bouwe P; Harris, Tamara B; et al. (PLoS One, 2015)
BACKGROUND: Hypertension is a major risk factor for a spectrum of cardiovascular diseases (CVD), including myocardial infarction, sudden death, and stroke. In the US, over 65 million people have high blood pressure and a large proportion of these individuals are prescribed antihypertensive medications. Although large long-term clinical trials conducted in the last several decades have identified a number of effective antihypertensive treatments that reduce the risk of future clinical complications, responses to therapy and protection from cardiovascular events vary among individuals. METHODS: Using a genome-wide association study among 21,267 participants with pharmaceutically treated hypertension, we explored the hypothesis that genetic variants might influence or modify the effectiveness of common antihypertensive therapies on the risk of major cardiovascular outcomes. The classes of drug treatments included angiotensin-converting enzyme inhibitors, beta-blockers, calcium channel blockers, and diuretics. In the setting of the Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) consortium, each study performed array-based genome-wide genotyping, imputed to HapMap Phase II reference panels, and used additive genetic models in proportional hazards or logistic regression models to evaluate drug-gene interactions for each of four therapeutic drug classes. We used meta-analysis to combine study-specific interaction estimates for approximately 2 million single nucleotide polymorphisms (SNPs) in a discovery analysis among 15,375 European Ancestry participants (3,527 CVD cases) with targeted follow-up in a case-only study of 1,751 European Ancestry GenHAT participants as well as among 4,141 African-Americans (1,267 CVD cases). RESULTS: Although drug-SNP interactions were biologically plausible, exposures and outcomes were well measured, and power was sufficient to detect modest interactions, we did not identify any statistically significant interactions from the four antihypertensive therapy meta-analyses (Pinteraction > 5.0×10-8). Similarly, findings were null for meta-analyses restricted to 66 SNPs with significant main effects on coronary artery disease or blood pressure from large published genome-wide association studies (Pinteraction ≥ 0.01). Our results suggest that there are no major pharmacogenetic influences of common SNPs on the relationship between blood pressure medications and the risk of incident CVD.
Keywords: African Americans; Aged; Antihypertensive Agents; Cardiovascular Diseases; European Continental Ancestry Group; Female; Genome-Wide Association Study; Humans; Hypertension; Incidence; Male; Middle Aged; Polymorphism, Single Nucleotide; Treatment Outcome

Exome sequencing identifies rare LDLR and APOA5 alleles conferring risk for myocardial infarction. - Do, Ron; Stitziel, Nathan O; Won, Hong-Hee; Jørgensen, Anders Berg; Duga, Stefano; Angelica Merlini, Pier; Kiezun, Adam; Farrall, Martin; Goel, Anuj; Zuk, Or; Guella, Illaria; Asselta, Rosanna; et al. (Nature, 2015)
Myocardial infarction (MI), a leading cause of death around the world, displays a complex pattern of inheritance. When MI occurs early in life, genetic inheritance is a major component to risk. Previously, rare mutations in low-density lipoprotein (LDL) genes have been shown to contribute to MI risk in individual families, whereas common variants at more than 45 loci have been associated with MI risk in the population. Here we evaluate how rare mutations contribute to early-onset MI risk in the population. We sequenced the protein-coding regions of 9,793 genomes from patients with MI at an early age (≤50 years in males and ≤60 years in females) along with MI-free controls. We identified two genes in which rare coding-sequence mutations were more frequent in MI cases versus controls at exome-wide significance. At low-density lipoprotein receptor (LDLR), carriers of rare non-synonymous mutations were at 4.2-fold increased risk for MI; carriers of null alleles at LDLR were at even higher risk (13-fold difference). Approximately 2% of early MI cases harbour a rare, damaging mutation in LDLR; this estimate is similar to one made more than 40 years ago using an analysis of total cholesterol. Among controls, about 1 in 217 carried an LDLR coding-sequence mutation and had plasma LDL cholesterol > 190 mg dl(-1). At apolipoprotein A-V (APOA5), carriers of rare non-synonymous mutations were at 2.2-fold increased risk for MI. When compared with non-carriers, LDLR mutation carriers had higher plasma LDL cholesterol, whereas APOA5 mutation carriers had higher plasma triglycerides. Recent evidence has connected MI risk with coding-sequence mutations at two genes functionally related to APOA5, namely lipoprotein lipase and apolipoprotein C-III (refs 18, 19). Combined, these observations suggest that, as well as LDL cholesterol, disordered metabolism of triglyceride-rich lipoproteins contributes to MI risk.
Keywords: Age Factors; Age of Onset; Alleles; Apolipoproteins A; Case-Control Studies; Cholesterol, LDL; Coronary Artery Disease; Exome; Female; Genetic Predisposition to Disease; Genetics, Population; Heterozygote; Humans; Male; Middle Aged; Mutation; Myocardial Infarction; National Heart, Lung, and Blood Institute (U.S.); Receptors, LDL; Triglycerides; United States

Fibrosis-related biomarkers and large and small vessel disease: the Cardiovascular Health Study. - Agarwal, Isha; Arnold, Alice; Glazer, Nicole L; Barasch, Eddy; Djoussé, Luc; Fitzpatrick, Annette L; Gottdiener, John S; Ix, Joachim H; Jensen, Richard A; Kizer, Jorge R; Rimm, Eric B; Siscovick, David S; et al. (Atherosclerosis, 2015)
OBJECTIVE: Fibrosis has been implicated in a number of pathological, organ-based conditions of the liver, kidney, heart, and lungs. The objective of this study was to determine whether biomarkers of fibrosis are associated with vascular disease in the large and/or small vessels. METHODS: We evaluated the associations of two circulating biomarkers of fibrosis, transforming growth factor-β (TGF-β) and procollagen type III N-terminal propeptide (PIIINP), with incident peripheral artery disease (PAD) and subclinical macrovascular (carotid intima-media thickness, flow-mediated vasodilation, ankle-brachial index, retinal vein diameter), and microvascular (retinal artery diameter and retinopathy) disease among older adults in the Cardiovascular Health Study. We measured TGF-β and PIIINP from samples collected in 1996 and ascertained clinical PAD through 2011. Measurements of large and small vessels were collected between 1996 and 1998. RESULTS: After adjustment for sociodemographic, clinical, and biochemical risk factors, TGF-β was associated with incident PAD (hazard ratio [HR] = 1.36 per doubling of TGF-β, 95% confidence interval [CI] = 1.04, 1.78) and retinal venular diameter (1.63 μm per doubling of TGF-β, CI = 0.23, 3.02). PIIINP was not associated with incident PAD, but was associated with carotid intima-media thickness (0.102 mm per doubling of PIIINP, CI = 0.029, 0.174) and impaired brachial artery reactivity (-0.20% change per doubling of PIIINP, CI = -0.39, -0.02). Neither TGF-β nor PIIINP were associated with retinal arteriolar diameter or retinopathy. CONCLUSIONS: Serum concentrations of fibrosis-related biomarkers were associated with several measures of large vessel disease, including incident PAD, but not with small vessel disease. Fibrosis may contribute to large vessel atherosclerosis in older adults.
Keywords: Aged; Ankle Brachial Index; Biomarkers; Brachial Artery; Carotid Artery Diseases; Carotid Intima-Media Thickness; Cross-Sectional Studies; Female; Fibrosis; Humans; Incidence; Male; Peptide Fragments; Peripheral Arterial Disease; Predictive Value of Tests; Procollagen; Prognosis; Prospective Studies; Retinal Diseases; Risk Factors; Transforming Growth Factor beta; United States; Vasodilation

Gene × dietary pattern interactions in obesity: analysis of up to 68 317 adults of European ancestry. - Nettleton, Jennifer A; Follis, Jack L; Ngwa, Julius S; Smith, Caren E; Ahmad, Shafqat; Tanaka, Toshiko; Wojczynski, Mary K; Voortman, Trudy; Lemaitre, Rozenn N; Kristiansson, Kati; Nuotio, Marja-Liisa; Houston, Denise K; et al. (Hum Mol Genet, 2015)
Obesity is highly heritable. Genetic variants showing robust associations with obesity traits have been identified through genome-wide association studies. We investigated whether a composite score representing healthy diet modifies associations of these variants with obesity traits. Totally, 32 body mass index (BMI)- and 14 waist-hip ratio (WHR)-associated single nucleotide polymorphisms were genotyped, and genetic risk scores (GRS) were calculated in 18 cohorts of European ancestry (n = 68 317). Diet score was calculated based on self-reported intakes of whole grains, fish, fruits, vegetables, nuts/seeds (favorable) and red/processed meats, sweets, sugar-sweetened beverages and fried potatoes (unfavorable). Multivariable adjusted, linear regression within each cohort followed by inverse variance-weighted, fixed-effects meta-analysis was used to characterize: (a) associations of each GRS with BMI and BMI-adjusted WHR and (b) diet score modification of genetic associations with BMI and BMI-adjusted WHR. Nominally significant interactions (P = 0.006-0.04) were observed between the diet score and WHR-GRS (but not BMI-GRS), two WHR loci (GRB14 rs10195252; LYPLAL1 rs4846567) and two BMI loci (LRRN6C rs10968576; MTIF3 rs4771122), for the respective BMI-adjusted WHR or BMI outcomes. Although the magnitudes of these select interactions were small, our data indicated that associations between genetic predisposition and obesity traits were stronger with a healthier diet. Our findings generate interesting hypotheses; however, experimental and functional studies are needed to determine their clinical relevance.
Keywords: Adult; Body Mass Index; Case-Control Studies; Diet, Western; Epistasis, Genetic; European Continental Ancestry Group; Female; Genetic Loci; Genome-Wide Association Study; Humans; Male; Obesity; Polymorphism, Single Nucleotide

Gene-centric approach identifies new and known loci for FVIII activity and VWF antigen levels in European Americans and African Americans. - Tang, Weihong; Cushman, Mary; Green, David; Rich, Stephen S; Lange, Leslie A; Yang, Qiong; Tracy, Russell P; Tofler, Geoffrey H; Basu, Saonli; Wilson, James G; Keating, Brendan J; Weng, Lu-Chen; et al. (Am J Hematol, 2015)
Coagulation factor VIII and von Willebrand factor (VWF) are key proteins in procoagulant activation. Higher FVIII coagulant activity (FVIII :C) and VWF antigen (VWF :Ag) are risk factors for cardiovascular disease and venous thromboembolism. Beyond associations with ABO blood group, genetic determinants of FVIII and VWF are not well understood, especially in non European-American populations. We performed a genetic association study of FVIII :C and VWF:Ag that assessed 50,000 gene-centric single nucleotide polymorphisms (SNPs) in 18,556 European Americans (EAs) and 5,047 African Americans (AAs) from five population-based cohorts. Previously unreported associations for FVIII :C were identified in both AAs and EAs with KNG1 (most significantly associated SNP rs710446, Ile581Thr, Ile581Thr, P = 5.10 × 10(-7) in EAs and P = 3.88 × 10(-3) in AAs) and VWF rs7962217 (Gly2705Arg,P = 6.30 × 10(-9) in EAs and P = 2.98 × 10(-2) in AAs. Significant associations for FVIII :C were also observed with F8/TMLHE region SNP rs12557310 in EAs (P = 8.02 × 10(-10) ), with VWF rs1800380 in AAs (P = 5.62 × 10(-11) ), and with MAT1A rs2236568 in AAs (P51.69 × 10(-6) ). We replicated previously reported associations of FVIII :C and VWF :Ag with the ABO blood group, VWF rs1063856(Thr789Ala), rs216321 (Ala852Gln), and VWF rs2229446 (Arg2185Gln). Findings from this study expand our understanding of genetic influences for FVIII :C and VWF :Ag in both EAs and AAs.
Keywords: Adult; African Americans; Aged; European Continental Ancestry Group; Factor VIII; Female; Genetic Loci; Genome-Wide Association Study; Humans; Male; Methionine Adenosyltransferase; Middle Aged; Polymorphism, Single Nucleotide; Venous Thromboembolism; von Willebrand Factor

Gene-Environment Interactions of Circadian-Related Genes for Cardiometabolic Traits. - Dashti, Hassan S; Follis, Jack L; Smith, Caren E; Tanaka, Toshiko; Garaulet, Marta; Gottlieb, Daniel J; Hruby, Adela; Jacques, Paul F; Kiefte-de Jong, Jessica C; Lamon-Fava, Stefania; Scheer, Frank A J L; Bartz, Traci M; et al. (Diabetes Care, 2015)
OBJECTIVE: Common circadian-related gene variants associate with increased risk for metabolic alterations including type 2 diabetes. However, little is known about whether diet and sleep could modify associations between circadian-related variants (CLOCK-rs1801260, CRY2-rs11605924, MTNR1B-rs1387153, MTNR1B-rs10830963, NR1D1-rs2314339) and cardiometabolic traits (fasting glucose [FG], HOMA-insulin resistance, BMI, waist circumference, and HDL-cholesterol) to facilitate personalized recommendations. RESEARCH DESIGN AND METHODS: We conducted inverse-variance weighted, fixed-effect meta-analyses of results of adjusted associations and interactions between dietary intake/sleep duration and selected variants on cardiometabolic traits from 15 cohort studies including up to 28,190 participants of European descent from the Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) Consortium. RESULTS: We observed significant associations between relative macronutrient intakes and glycemic traits and short sleep duration (<7 h) and higher FG and replicated known MTNR1B associations with glycemic traits. No interactions were evident after accounting for multiple comparisons. However, we observed nominally significant interactions (all P < 0.01) between carbohydrate intake and MTNR1B-rs1387153 for FG with a 0.003 mmol/L higher FG with each additional 1% carbohydrate intake in the presence of the T allele, between sleep duration and CRY2-rs11605924 for HDL-cholesterol with a 0.010 mmol/L higher HDL-cholesterol with each additional hour of sleep in the presence of the A allele, and between long sleep duration (≥9 h) and MTNR1B-rs1387153 for BMI with a 0.60 kg/m(2) higher BMI with long sleep duration in the presence of the T allele relative to normal sleep duration (≥7 to <9 h). CONCLUSIONS: Our results suggest that lower carbohydrate intake and normal sleep duration may ameliorate cardiometabolic abnormalities conferred by common circadian-related genetic variants. Until further mechanistic examination of the nominally significant interactions is conducted, recommendations applicable to the general population regarding diet—specifically higher carbohydrate and lower fat composition—and normal sleep duration should continue to be emphasized among individuals with the investigated circadian-related gene variants.
Keywords: Adult; Alleles; Blood Glucose; Circadian Rhythm Signaling Peptides and Proteins; Cohort Studies; Diabetes Mellitus, Type 2; Diet, Fat-Restricted; European Continental Ancestry Group; Fasting; Female; Gene-Environment Interaction; Humans; Insulin Resistance; Male; Middle Aged; Multicenter Studies as Topic; Observational Studies as Topic; Phenotype; Polymorphism, Single Nucleotide; Sleep; Waist Circumference

Generalized estimating equations for genome-wide association studies using longitudinal phenotype data. - Sitlani, Colleen M; Rice, Kenneth M; Lumley, Thomas; McKnight, Barbara; Cupples, L Adrienne; Avery, Christy L; Noordam, Raymond; Stricker, Bruno H C; Whitsel, Eric A; Psaty, Bruce M (Stat Med, 2015)
Many longitudinal cohort studies have both genome-wide measures of genetic variation and repeated measures of phenotypes and environmental exposures. Genome-wide association study analyses have typically used only cross-sectional data to evaluate quantitative phenotypes and binary traits. Incorporation of repeated measures may increase power to detect associations, but also requires specialized analysis methods. Here, we discuss one such method-generalized estimating equations (GEE)-in the contexts of analysis of main effects of rare genetic variants and analysis of gene-environment interactions. We illustrate the potential for increased power using GEE analyses instead of cross-sectional analyses. We also address challenges that arise, such as the need for small-sample corrections when the minor allele frequency of a genetic variant and/or the prevalence of an environmental exposure is low. To illustrate methods for detection of gene-drug interactions on a genome-wide scale, using repeated measures data, we conduct single-study analyses and meta-analyses across studies in three large cohort studies participating in the Cohorts for Heart and Aging Research in Genomic Epidemiology consortium-the Atherosclerosis Risk in Communities study, the Cardiovascular Health Study, and the Rotterdam Study.
Keywords: Aged; Aging; Cardiovascular Diseases; Cohort Studies; Computer Simulation; Cross-Sectional Studies; Epidemiologic Research Design; Gene-Environment Interaction; Genetic Variation; Genome, Human; Genome-Wide Association Study; Humans; Longitudinal Studies; Meta-Analysis as Topic; Models, Genetic; Pharmacogenetics; Risk Assessment; United States

Genes from a translational analysis support a multifactorial nature of white matter hyperintensities. - Lopez, Lorna M; Hill, W David; Harris, Sarah E; Valdes Hernandez, Maria; Munoz Maniega, Susana; Bastin, Mark E; Bailey, Emma; Smith, Colin; McBride, Martin; McClure, John; Graham, Delyth; Dominiczak, Anna; et al. (Stroke, 2015)
BACKGROUND AND PURPOSE: White matter hyperintensities (WMH) of presumed vascular origin increase the risk of stroke and dementia. Despite strong WMH heritability, few gene associations have been identified. Relevant experimental models may be informative. METHODS: We tested the associations between genes that were differentially expressed in brains of young spontaneously hypertensive stroke-prone rats and human WMH (using volume and visual score) in 621 subjects from the Lothian Birth Cohort 1936 (LBC1936). We then attempted replication in 9361 subjects from the Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE). We also tested the subjects from LBC1936 for previous genome-wide WMH associations found in subjects from CHARGE. RESULTS: Of 126 spontaneously hypertensive stroke-prone rat genes, 10 were nominally associated with WMH volume or score in subjects from LBC1936, of which 5 (AFP, ALB, GNAI1, RBM8a, and MRPL18) were associated with both WMH volume and score (P<0.05); 2 of the 10 (XPNPEP1, P=6.7×10(-5); FARP1, P=0.024) plus another spontaneously hypertensive stroke-prone rat gene (USMG5, P=0.00014), on chromosomes 10, 13, and 10 respectively, were associated with WMH in subjects from CHARGE. Gene set enrichment showed significant associations for downregulated spontaneously hypertensive stroke-prone rat genes with WMH in humans. In subjects from LBC1936, we replicated CHARGE's genome-wide WMH associations on chromosomes 17 (TRIM65 and TRIM47) and, for the first time, 1 (PMF1). CONCLUSIONS: Despite not passing multiple testing thresholds individually, these genes collectively are relevant to known WMH associations, proposed WMH mechanisms, or dementia: associations with Alzheimer's disease, late-life depression, ATP production, osmotic regulation, neurodevelopmental abnormalities, and cognitive impairment. If replicated further, they suggest a multifactorial nature for WMH and argue for more consideration of vascular contributions to dementia.
Keywords: Aged; Alzheimer Disease; Animals; Brain; Causality; Dementia; Female; Genome-Wide Association Study; Humans; Leukoencephalopathies; Male; Polymorphism, Single Nucleotide; Rats; Rats, Inbred SHR; Rats, Wistar; Risk Factors; Translational Medical Research; White Matter

Genetic contributions to variation in general cognitive function: a meta-analysis of genome-wide association studies in the CHARGE consortium (N=53949). - Davies, G; Armstrong, N; Bis, J C; Bressler, J; Chouraki, V; Giddaluru, S; Hofer, E; Ibrahim-Verbaas, C A; Kirin, M; Lahti, J; van der Lee, S J; Le Hellard, S; et al. (Mol Psychiatry, 2015)
General cognitive function is substantially heritable across the human life course from adolescence to old age. We investigated the genetic contribution to variation in this important, health- and well-being-related trait in middle-aged and older adults. We conducted a meta-analysis of genome-wide association studies of 31 cohorts (N=53,949) in which the participants had undertaken multiple, diverse cognitive tests. A general cognitive function phenotype was tested for, and created in each cohort by principal component analysis. We report 13 genome-wide significant single-nucleotide polymorphism (SNP) associations in three genomic regions, 6q16.1, 14q12 and 19q13.32 (best SNP and closest gene, respectively: rs10457441, P=3.93 × 10(-9), MIR2113; rs17522122, P=2.55 × 10(-8), AKAP6; rs10119, P=5.67 × 10(-9), APOE/TOMM40). We report one gene-based significant association with the HMGN1 gene located on chromosome 21 (P=1 × 10(-6)). These genes have previously been associated with neuropsychiatric phenotypes. Meta-analysis results are consistent with a polygenic model of inheritance. To estimate SNP-based heritability, the genome-wide complex trait analysis procedure was applied to two large cohorts, the Atherosclerosis Risk in Communities Study (N=6617) and the Health and Retirement Study (N=5976). The proportion of phenotypic variation accounted for by all genotyped common SNPs was 29% (s.e.=5%) and 28% (s.e.=7%), respectively. Using polygenic prediction analysis, ~1.2% of the variance in general cognitive function was predicted in the Generation Scotland cohort (N=5487; P=1.5 × 10(-17)). In hypothesis-driven tests, there was significant association between general cognitive function and four genes previously associated with Alzheimer's disease: TOMM40, APOE, ABCG1 and MEF2C.
Keywords: Aged; Aged, 80 and over; Atherosclerosis; Cognition; Cognition Disorders; Cohort Studies; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; HMGN1 Protein; Humans; Male; Middle Aged; Neuropsychological Tests; Phenotype; Polymorphism, Single Nucleotide; Scotland

Genetic loci associated with circulating levels of very long-chain saturated fatty acids. - Lemaitre, Rozenn N; King, Irena B; Kabagambe, Edmond K; Wu, Jason H Y; McKnight, Barbara; Manichaikul, Ani; Guan, Weihua; Sun, Qi; Chasman, Daniel I; Foy, Millennia; Wang, Lu; Zhu, Jingwen; et al. (J Lipid Res, 2015)
Very long-chain saturated fatty acids (VLSFAs) are saturated fatty acids with 20 or more carbons. In contrast to the more abundant saturated fatty acids, such as palmitic acid, there is growing evidence that circulating VLSFAs may have beneficial biological properties. Whether genetic factors influence circulating levels of VLSFAs is not known. We investigated the association of common genetic variation with plasma phospholipid/erythrocyte levels of three VLSFAs by performing genome-wide association studies in seven population-based cohorts comprising 10,129 subjects of European ancestry. We observed associations of circulating VLSFA concentrations with common variants in two genes, serine palmitoyl-transferase long-chain base subunit 3 (SPTLC3), a gene involved in the rate-limiting step of de novo sphingolipid synthesis, and ceramide synthase 4 (CERS4). The SPTLC3 variant at rs680379 was associated with higher arachidic acid (20:0 , P = 5.81 × 10(-13)). The CERS4 variant at rs2100944 was associated with higher levels of 20:0 (P = 2.65 × 10(-40)) and in analyses that adjusted for 20:0, with lower levels of behenic acid (P = 4.22 × 10(-26)) and lignoceric acid (P = 3.20 × 10(-21)). These novel associations suggest an inter-relationship of circulating VLSFAs and sphingolipid synthesis.
Keywords: Cohort Studies; Fatty Acids; Genetic Loci; Genetic Variation; Genome-Wide Association Study; Humans

Genetic loci associated with circulating phospholipid trans fatty acids: a meta-analysis of genome-wide association studies from the CHARGE Consortium. - Mozaffarian, Dariush; Kabagambe, Edmond K; Johnson, Catherine O; Lemaitre, Rozenn N; Manichaikul, Ani; Sun, Qi; Foy, Millennia; Wang, Lu; Wiener, Howard; Irvin, Marguerite R; Rich, Stephen S; Wu, Hongyu; et al. (Am J Clin Nutr, 2015)
BACKGROUND: Circulating trans fatty acids (TFAs), which cannot be synthesized by humans, are linked to adverse health outcomes. Although TFAs are obtained from diet, little is known about subsequent influences (e.g., relating to incorporation, metabolism, or intercompetition with other fatty acids) that could alter circulating concentrations and possibly modulate or mediate impacts on health. OBJECTIVE: The objective was to elucidate novel biologic pathways that may influence circulating TFAs by evaluating associations between common genetic variation and TFA biomarkers. DESIGN: We performed meta-analyses using 7 cohorts of European-ancestry participants (n = 8013) having measured genome-wide variation in single-nucleotide polymorphisms (SNPs) and circulating TFA biomarkers (erythrocyte or plasma phospholipids), including trans-16:1n-7, total trans-18:1, trans/cis-18:2, cis/trans-18:2, and trans/trans-18:2. We further evaluated SNPs with genome-wide significant associations among African Americans (n = 1082), Chinese Americans (n = 669), and Hispanic Americans (n = 657) from 2 of these cohorts. RESULTS: Among European-ancestry participants, 31 SNPs in or near the fatty acid desaturase (FADS) 1 and 2 cluster were associated with cis/trans-18:2; a top hit was rs174548 (β = 0.0035, P = 4.90 × 10(-15)), an SNP previously associated with circulating n-3 and n-6 polyunsaturated fatty acid concentrations. No significant association was identified for other TFAs. rs174548 in FADS1/2 was also associated with cis/trans-18:2 in Hispanic Americans (β = 0.0053, P = 1.05 × 10(-6)) and Chinese Americans (β = 0.0028, P = 0.002) but not African Americans (β = 0.0009, P = 0.34); however, in African Americans, fine mapping identified a top hit in FADS2 associated with cis/trans-18:2 (rs174579: β = 0.0118, P = 4.05 × 10(-5)). The association between rs174548 and cis/trans-18:2 remained significant after further adjustment for individual circulating n-3 and n-6 fatty acids, except arachidonic acid. After adjustment for arachidonic acid concentrations, the association between rs174548 and cis/trans-18:2 was nearly eliminated in European-ancestry participants (β-coefficient reduced by 86%), with similar reductions in Hispanic Americans and Chinese Americans. CONCLUSIONS: Our findings provide novel evidence for genetic regulation of cis/trans-18:2 by the FADS1/2 cluster and suggest that this regulation may be influenced/mediated by concentrations of arachidonic acid, an n-6 polyunsaturated fat.
Keywords: African Americans; Arachidonic Acid; Asian Americans; Biomarkers; European Continental Ancestry Group; Fatty Acids, Omega-6; Gene Frequency; Genetic Association Studies; Genetic Loci; Genotyping Techniques; Humans; Phospholipids; Polymorphism, Single Nucleotide; Trans Fatty Acids

Genetic overlap between diagnostic subtypes of ischemic stroke. - Holliday, Elizabeth G; Traylor, Matthew; Malik, Rainer; Bevan, Steve; Falcone, Guido; Hopewell, Jemma C; Cheng, Yu-Ching; Cotlarciuc, Ioana; Bis, Joshua C; Boerwinkle, Eric; Boncoraglio, Giorgio B; Clarke, Robert; et al. (Stroke, 2015)
BACKGROUND AND PURPOSE: Despite moderate heritability, the phenotypic heterogeneity of ischemic stroke has hampered gene discovery, motivating analyses of diagnostic subtypes with reduced sample sizes. We assessed evidence for a shared genetic basis among the 3 major subtypes: large artery atherosclerosis (LAA), cardioembolism, and small vessel disease (SVD), to inform potential cross-subtype analyses. METHODS: Analyses used genome-wide summary data for 12 389 ischemic stroke cases (including 2167 LAA, 2405 cardioembolism, and 1854 SVD) and 62 004 controls from the Metastroke consortium. For 4561 cases and 7094 controls, individual-level genotype data were also available. Genetic correlations between subtypes were estimated using linear mixed models and polygenic profile scores. Meta-analysis of a combined LAA-SVD phenotype (4021 cases and 51 976 controls) was performed to identify shared risk alleles. RESULTS: High genetic correlation was identified between LAA and SVD using linear mixed models (rg=0.96, SE=0.47, P=9×10(-4)) and profile scores (rg=0.72; 95% confidence interval, 0.52-0.93). Between LAA and cardioembolism and SVD and cardioembolism, correlation was moderate using linear mixed models but not significantly different from zero for profile scoring. Joint meta-analysis of LAA and SVD identified strong association (P=1×10(-7)) for single nucleotide polymorphisms near the opioid receptor μ1 (OPRM1) gene. CONCLUSIONS: Our results suggest that LAA and SVD, which have been hitherto treated as genetically distinct, may share a substantial genetic component. Combined analyses of LAA and SVD may increase power to identify small-effect alleles influencing shared pathophysiological processes.
Keywords: Alleles; Atherosclerosis; Cerebral Small Vessel Diseases; Cohort Studies; Data Interpretation, Statistical; Embolism; Genome-Wide Association Study; Genotype; Humans; Ischemia; Linear Models; Meta-Analysis as Topic; Phenotype; Polymorphism, Single Nucleotide; Stroke

Genome of The Netherlands population-specific imputations identify an ABCA6 variant associated with cholesterol levels. - van Leeuwen, Elisabeth M; Karssen, Lennart C; Deelen, Joris; Isaacs, Aaron; Medina-Gómez, Carolina; Mbarek, Hamdi; Kanterakis, Alexandros; Trompet, Stella; Postmus, Iris; Verweij, Niek; van Enckevort, David J; Huffman, Jennifer E; et al. (Nat Commun, 2015)
Variants associated with blood lipid levels may be population-specific. To identify low-frequency variants associated with this phenotype, population-specific reference panels may be used. Here we impute nine large Dutch biobanks (~35,000 samples) with the population-specific reference panel created by the Genome of The Netherlands Project and perform association testing with blood lipid levels. We report the discovery of five novel associations at four loci (P value <6.61 × 10(-4)), including a rare missense variant in ABCA6 (rs77542162, p.Cys1359Arg, frequency 0.034), which is predicted to be deleterious. The frequency of this ABCA6 variant is 3.65-fold increased in the Dutch and its effect (βLDL-C=0.135, βTC=0.140) is estimated to be very similar to those observed for single variants in well-known lipid genes, such as LDLR.
Keywords: ATP-Binding Cassette Transporters; Cholesterol; Gene Frequency; Genetic Association Studies; Humans; Mutation, Missense; Netherlands

Genome-Wide Association Study and Linkage Analysis of the Healthy Aging Index. - Minster, Ryan L; Sanders, Jason L; Singh, Jatinder; Kammerer, Candace M; Barmada, M Michael; Matteini, Amy M; Zhang, Qunyuan; Wojczynski, Mary K; Daw, E Warwick; Brody, Jennifer A; Arnold, Alice M; Lunetta, Kathryn L; et al. (J Gerontol A Biol Sci Med Sci, 2015)
BACKGROUND: The Healthy Aging Index (HAI) is a tool for measuring the extent of health and disease across multiple systems. METHODS: We conducted a genome-wide association study and a genome-wide linkage analysis to map quantitative trait loci associated with the HAI and a modified HAI weighted for mortality risk in 3,140 individuals selected for familial longevity from the Long Life Family Study. The genome-wide association study used the Long Life Family Study as the discovery cohort and individuals from the Cardiovascular Health Study and the Framingham Heart Study as replication cohorts. RESULTS: There were no genome-wide significant findings from the genome-wide association study; however, several single-nucleotide polymorphisms near ZNF704 on chromosome 8q21.13 were suggestively associated with the HAI in the Long Life Family Study (p < 10(-) (6)) and nominally replicated in the Cardiovascular Health Study and Framingham Heart Study. Linkage results revealed significant evidence (log-odds score = 3.36) for a quantitative trait locus for mortality-optimized HAI in women on chromosome 9p24-p23. However, results of fine-mapping studies did not implicate any specific candidate genes within this region of interest. CONCLUSIONS: ZNF704 may be a potential candidate gene for studies of the genetic underpinnings of longevity.
Keywords: Aging; Apolipoproteins E; Forkhead Transcription Factors; Genetic Linkage; Genome-Wide Association Study; Humans; Longevity; Polymorphism, Single Nucleotide; Quantitative Trait Loci

Genome-wide meta-analysis identifies six novel loci associated with habitual coffee consumption. - Cornelis, M C; Byrne, E M; Esko, T; Nalls, M A; Ganna, A; Paynter, N; Monda, K L; Amin, N; Fischer, K; Renstrom, F; Ngwa, J S; Huikari, V; et al. (Mol Psychiatry, 2015)
Coffee, a major dietary source of caffeine, is among the most widely consumed beverages in the world and has received considerable attention regarding health risks and benefits. We conducted a genome-wide (GW) meta-analysis of predominately regular-type coffee consumption (cups per day) among up to 91,462 coffee consumers of European ancestry with top single-nucleotide polymorphisms (SNPs) followed-up in ~30 062 and 7964 coffee consumers of European and African-American ancestry, respectively. Studies from both stages were combined in a trans-ethnic meta-analysis. Confirmed loci were examined for putative functional and biological relevance. Eight loci, including six novel loci, met GW significance (log10Bayes factor (BF)>5.64) with per-allele effect sizes of 0.03-0.14 cups per day. Six are located in or near genes potentially involved in pharmacokinetics (ABCG2, AHR, POR and CYP1A2) and pharmacodynamics (BDNF and SLC6A4) of caffeine. Two map to GCKR and MLXIPL genes related to metabolic traits but lacking known roles in coffee consumption. Enhancer and promoter histone marks populate the regions of many confirmed loci and several potential regulatory SNPs are highly correlated with the lead SNP of each. SNP alleles near GCKR, MLXIPL, BDNF and CYP1A2 that were associated with higher coffee consumption have previously been associated with smoking initiation, higher adiposity and fasting insulin and glucose but lower blood pressure and favorable lipid, inflammatory and liver enzyme profiles (P<5 × 10(-8)).Our genetic findings among European and African-American adults reinforce the role of caffeine in mediating habitual coffee consumption and may point to molecular mechanisms underlying inter-individual variability in pharmacological and health effects of coffee.
Keywords: Adaptor Proteins, Signal Transducing; Basic Helix-Loop-Helix Leucine Zipper Transcription Factors; Brain-Derived Neurotrophic Factor; Coffea; Cytochrome P-450 CYP1A2; Food Habits; Genome-Wide Association Study; Humans; Phenotype; Polymorphism, Single Nucleotide

Genome-wide studies of verbal declarative memory in nondemented older people: the Cohorts for Heart and Aging Research in Genomic Epidemiology consortium. - Debette, Stephanie; Ibrahim Verbaas, Carla A; Bressler, Jan; Schuur, Maaike; Smith, Albert; Bis, Joshua C; Davies, Gail; Wolf, Christiane; Gudnason, Vilmundur; Chibnik, Lori B; Yang, Qiong; DeStefano, Anita L; et al. (Biol Psychiatry, 2015)
BACKGROUND: Memory performance in older persons can reflect genetic influences on cognitive function and dementing processes. We aimed to identify genetic contributions to verbal declarative memory in a community setting. METHODS: We conducted genome-wide association studies for paragraph or word list delayed recall in 19 cohorts from the Cohorts for Heart and Aging Research in Genomic Epidemiology consortium, comprising 29,076 dementia- and stroke-free individuals of European descent, aged ≥45 years. Replication of suggestive associations (p < 5 × 10(-6)) was sought in 10,617 participants of European descent, 3811 African-Americans, and 1561 young adults. RESULTS: rs4420638, near APOE, was associated with poorer delayed recall performance in discovery (p = 5.57 × 10(-10)) and replication cohorts (p = 5.65 × 10(-8)). This association was stronger for paragraph than word list delayed recall and in the oldest persons. Two associations with specific tests, in subsets of the total sample, reached genome-wide significance in combined analyses of discovery and replication (rs11074779 [HS3ST4], p = 3.11 × 10(-8), and rs6813517 [SPOCK3], p = 2.58 × 10(-8)) near genes involved in immune response. A genetic score combining 58 independent suggestive memory risk variants was associated with increasing Alzheimer disease pathology in 725 autopsy samples. Association of memory risk loci with gene expression in 138 human hippocampus samples showed cis-associations with WDR48 and CLDN5, both related to ubiquitin metabolism. CONCLUSIONS: This largest study to date exploring the genetics of memory function in ~40,000 older individuals revealed genome-wide associations and suggested an involvement of immune and ubiquitin pathways.
Keywords: Aged; Aged, 80 and over; Aging; Apolipoproteins E; Claudin-5; Cohort Studies; Female; Genome-Wide Association Study; Genotype; Humans; Male; Memory Disorders; Middle Aged; Polymorphism, Single Nucleotide; Proteins; Proteoglycans; Regression Analysis; Sulfotransferases; Verbal Learning

GWAS of longevity in CHARGE consortium confirms APOE and FOXO3 candidacy. - Broer, Linda; Buchman, Aron S; Deelen, Joris; Evans, Daniel S; Faul, Jessica D; Lunetta, Kathryn L; Sebastiani, Paola; Smith, Jennifer A; Smith, Albert V; Tanaka, Toshiko; Yu, Lei; Arnold, Alice M; et al. (J Gerontol A Biol Sci Med Sci, 2015)
BACKGROUND: The genetic contribution to longevity in humans has been estimated to range from 15% to 25%. Only two genes, APOE and FOXO3, have shown association with longevity in multiple independent studies. METHODS: We conducted a meta-analysis of genome-wide association studies including 6,036 longevity cases, age ≥90 years, and 3,757 controls that died between ages 55 and 80 years. We additionally attempted to replicate earlier identified single nucleotide polymorphism (SNP) associations with longevity. RESULTS: In our meta-analysis, we found suggestive evidence for the association of SNPs near CADM2 (odds ratio [OR] = 0.81; p value = 9.66 × 10(-7)) and GRIK2 (odds ratio = 1.24; p value = 5.09 × 10(-8)) with longevity. When attempting to replicate findings earlier identified in genome-wide association studies, only the APOE locus consistently replicated. In an additional look-up of the candidate gene FOXO3, we found that an earlier identified variant shows a highly significant association with longevity when including published data with our meta-analysis (odds ratio = 1.17; p value = 1.85×10(-10)). CONCLUSIONS: We did not identify new genome-wide significant associations with longevity and did not replicate earlier findings except for APOE and FOXO3. Our inability to find new associations with survival to ages ≥90 years because longevity represents multiple complex traits with heterogeneous genetic underpinnings, or alternatively, that longevity may be regulated by rare variants that are not captured by standard genome-wide genotyping and imputation of common variants.
Keywords: Aged; Aged, 80 and over; Apolipoproteins E; Cell Adhesion Molecules; Cohort Studies; Female; Forkhead Box Protein O3; Forkhead Transcription Factors; Genome-Wide Association Study; Humans; Longevity; Male; Middle Aged; Polymorphism, Single Nucleotide; Receptors, Kainic Acid

HMG-coenzyme A reductase inhibition, type 2 diabetes, and bodyweight: evidence from genetic analysis and randomised trials. - Swerdlow, Daniel I; Preiss, David; Kuchenbaecker, Karoline B; Holmes, Michael V; Engmann, Jorgen E L; Shah, Tina; Sofat, Reecha; Stender, Stefan; Johnson, Paul C D; Scott, Robert A; Leusink, Maarten; Verweij, Niek; et al. (Lancet, 2015)
BACKGROUND: Statins increase the risk of new-onset type 2 diabetes mellitus. We aimed to assess whether this increase in risk is a consequence of inhibition of 3-hydroxy-3-methylglutaryl-CoA reductase (HMGCR), the intended drug target. METHODS: We used single nucleotide polymorphisms in the HMGCR gene, rs17238484 (for the main analysis) and rs12916 (for a subsidiary analysis) as proxies for HMGCR inhibition by statins. We examined associations of these variants with plasma lipid, glucose, and insulin concentrations; bodyweight; waist circumference; and prevalent and incident type 2 diabetes. Study-specific effect estimates per copy of each LDL-lowering allele were pooled by meta-analysis. These findings were compared with a meta-analysis of new-onset type 2 diabetes and bodyweight change data from randomised trials of statin drugs. The effects of statins in each randomised trial were assessed using meta-analysis. FINDINGS: Data were available for up to 223 463 individuals from 43 genetic studies. Each additional rs17238484-G allele was associated with a mean 0·06 mmol/L (95% CI 0·05-0·07) lower LDL cholesterol and higher body weight (0·30 kg, 0·18-0·43), waist circumference (0·32 cm, 0·16-0·47), plasma insulin concentration (1·62%, 0·53-2·72), and plasma glucose concentration (0·23%, 0·02-0·44). The rs12916 SNP had similar effects on LDL cholesterol, bodyweight, and waist circumference. The rs17238484-G allele seemed to be associated with higher risk of type 2 diabetes (odds ratio [OR] per allele 1·02, 95% CI 1·00-1·05); the rs12916-T allele association was consistent (1·06, 1·03-1·09). In 129 170 individuals in randomised trials, statins lowered LDL cholesterol by 0·92 mmol/L (95% CI 0·18-1·67) at 1-year of follow-up, increased bodyweight by 0·24 kg (95% CI 0·10-0·38 in all trials; 0·33 kg, 95% CI 0·24-0·42 in placebo or standard care controlled trials and -0·15 kg, 95% CI -0·39 to 0·08 in intensive-dose vs moderate-dose trials) at a mean of 4·2 years (range 1·9-6·7) of follow-up, and increased the odds of new-onset type 2 diabetes (OR 1·12, 95% CI 1·06-1·18 in all trials; 1·11, 95% CI 1·03-1·20 in placebo or standard care controlled trials and 1·12, 95% CI 1·04-1·22 in intensive-dose vs moderate dose trials). INTERPRETATION: The increased risk of type 2 diabetes noted with statins is at least partially explained by HMGCR inhibition. FUNDING: The funding sources are cited at the end of the paper.
Keywords: Aged; Body Mass Index; Body Weight; Cholesterol, HDL; Cholesterol, LDL; Diabetes Mellitus, Type 2; Female; Genetic Testing; Humans; Hydroxymethylglutaryl CoA Reductases; Hydroxymethylglutaryl-CoA Reductase Inhibitors; Male; Middle Aged; Polymorphism, Single Nucleotide; Randomized Controlled Trials as Topic; Risk Factors

Integrative pathway genomics of lung function and airflow obstruction. - Gharib, Sina A; Loth, Daan W; Soler Artigas, Maria; Birkland, Timothy P; Wilk, Jemma B; Wain, Louise V; Brody, Jennifer A; Obeidat, Ma'en; Hancock, Dana B; Tang, Wenbo; Rawal, Rajesh; Boezen, H Marike; et al. (Hum Mol Genet, 2015)
Chronic respiratory disorders are important contributors to the global burden of disease. Genome-wide association studies (GWASs) of lung function measures have identified several trait-associated loci, but explain only a modest portion of the phenotypic variability. We postulated that integrating pathway-based methods with GWASs of pulmonary function and airflow obstruction would identify a broader repertoire of genes and processes influencing these traits. We performed two independent GWASs of lung function and applied gene set enrichment analysis to one of the studies and validated the results using the second GWAS. We identified 131 significantly enriched gene sets associated with lung function and clustered them into larger biological modules involved in diverse processes including development, immunity, cell signaling, proliferation and arachidonic acid. We found that enrichment of gene sets was not driven by GWAS-significant variants or loci, but instead by those with less stringent association P-values. Next, we applied pathway enrichment analysis to a meta-analyzed GWAS of airflow obstruction. We identified several biologic modules that functionally overlapped with those associated with pulmonary function. However, differences were also noted, including enrichment of extracellular matrix (ECM) processes specifically in the airflow obstruction study. Network analysis of the ECM module implicated a candidate gene, matrix metalloproteinase 10 (MMP10), as a putative disease target. We used a knockout mouse model to functionally validate MMP10's role in influencing lung's susceptibility to cigarette smoke-induced emphysema. By integrating pathway analysis with population-based genomics, we unraveled biologic processes underlying pulmonary function traits and identified a candidate gene for obstructive lung disease.
Keywords: Airway Obstruction; Animals; Cell Proliferation; European Continental Ancestry Group; Genetic Predisposition to Disease; Genome-Wide Association Study; Genomics; Humans; Immune System; Lung; Male; Metabolic Networks and Pathways; Mice; Phenotype; Polymorphism, Single Nucleotide; Signal Transduction

Low-frequency and rare exome chip variants associate with fasting glucose and type 2 diabetes susceptibility. - Wessel, Jennifer; Chu, Audrey Y; Willems, Sara M; Wang, Shuai; Yaghootkar, Hanieh; Brody, Jennifer A; Dauriz, Marco; Hivert, Marie-France; Raghavan, Sridharan; Lipovich, Leonard; Hidalgo, Bertha; Fox, Keolu; et al. (Nat Commun, 2015)
Fasting glucose and insulin are intermediate traits for type 2 diabetes. Here we explore the role of coding variation on these traits by analysis of variants on the HumanExome BeadChip in 60,564 non-diabetic individuals and in 16,491 T2D cases and 81,877 controls. We identify a novel association of a low-frequency nonsynonymous SNV in GLP1R (A316T; rs10305492; MAF=1.4%) with lower FG (β=-0.09±0.01 mmol l(-1), P=3.4 × 10(-12)), T2D risk (OR[95%CI]=0.86[0.76-0.96], P=0.010), early insulin secretion (β=-0.07±0.035 pmolinsulin mmolglucose(-1), P=0.048), but higher 2-h glucose (β=0.16±0.05 mmol l(-1), P=4.3 × 10(-4)). We identify a gene-based association with FG at G6PC2 (pSKAT=6.8 × 10(-6)) driven by four rare protein-coding SNVs (H177Y, Y207S, R283X and S324P). We identify rs651007 (MAF=20%) in the first intron of ABO at the putative promoter of an antisense lncRNA, associating with higher FG (β=0.02±0.004 mmol l(-1), P=1.3 × 10(-8)). Our approach identifies novel coding variant associations and extends the allelic spectrum of variation underlying diabetes-related quantitative traits and T2D susceptibility.
Keywords: African Continental Ancestry Group; Blood Glucose; Diabetes Mellitus, Type 2; European Continental Ancestry Group; Exome; Fasting; Genetic Association Studies; Genetic Loci; Genetic Predisposition to Disease; Genetic Variation; Glucagon-Like Peptide-1 Receptor; Glucose-6-Phosphatase; Humans; Insulin; Mutation Rate; Oligonucleotide Array Sequence Analysis; Polymorphism, Single Nucleotide

LV Mass as a Predictor of CVD Events in Older Adults With and Without Metabolic Syndrome and Diabetes. - Hoang, Khiet; Zhao, Yanglu; Gardin, Julius M; Carnethon, Mercedes; Mukamal, Ken; Yanez, David; Wong, Nathan D (JACC Cardiovasc Imaging, 2015)
OBJECTIVES: The purpose of this study was to examine the prognostic significance of left ventricular (LV) mass for cardiovascular disease (CVD) events in older adults with and without metabolic syndrome (MetS) and diabetes mellitus (DM). BACKGROUND: MetS and DM are associated with increased CVD risk, but it is unclear in these groups whether subclinical CVD as shown by increased LV mass improves risk prediction compared to standard risk factors in older individuals. METHODS: We studied 3,724 adults (mean 72.4 ± 5.4 years of age, 61.0% female, 4.4% African-American) from the Cardiovascular Health Study who had MetS but not DM or had DM alone or had neither condition. Cox regression was used to examine the association of LV mass, (alone and indexed by height and body surface area [BSA]) as determined by echocardiography, with CVD events, including coronary heart disease (CHD), stroke, heart failure (HF), and CVD death, as well as total mortality. We also assessed the added prediction, discriminative value, and net reclassification improvement (NRI) for clinical utility of LV mass compared to standard risk factors. RESULTS: Over a mean follow-up of 14.2 ± 6.3 years, 2,180 subjects experienced CVD events, including 986 CVD deaths. After adjustment for age, sex and standard risk factors, LV mass was positively associated with CVD events in those with MetS (hazard ratio [HR]: 1.4, p < 0.001) and without MetS (HR: 1.4, p < 0.001), but not DM (HR: 1.0, p = 0.62), with similar findings for LV mass indexed for height or BSA. Adding LV mass to standard risk factors moderately improved the prediction accuracy in the overall sample and MetS group from changes in C-statistics (p < 0.05). Categorical-free net reclassification improvement increased significantly by 17% to 19% in those with MetS. Findings were comparable for CHD, CVD mortality, and total mortality. CONCLUSIONS: LV mass is associated with increased CVD risk and provides modest added prediction and clinical utility compared to standard risk factors in older persons with and without MetS but not with DM.
Keywords: Aged; Aged, 80 and over; Cardiovascular Diseases; Comorbidity; Diabetes Mellitus; Female; Heart Ventricles; Humans; Hypertrophy, Left Ventricular; Logistic Models; Male; Metabolic Syndrome X; Prognosis; Proportional Hazards Models; Prospective Studies; Risk Assessment; Risk Factors; Time Factors; United States

Mendelian randomization of blood lipids for coronary heart disease. - Holmes, Michael V; Asselbergs, Folkert W; Palmer, Tom M; Drenos, Fotios; Lanktree, Matthew B; Nelson, Christopher P; Dale, Caroline E; Padmanabhan, Sandosh; Finan, Chris; Swerdlow, Daniel I; Tragante, Vinicius; van Iperen, Erik P A; et al. (Eur Heart J, 2015)
AIMS: To investigate the causal role of high-density lipoprotein cholesterol (HDL-C) and triglycerides in coronary heart disease (CHD) using multiple instrumental variables for Mendelian randomization. METHODS AND RESULTS: We developed weighted allele scores based on single nucleotide polymorphisms (SNPs) with established associations with HDL-C, triglycerides, and low-density lipoprotein cholesterol (LDL-C). For each trait, we constructed two scores. The first was unrestricted, including all independent SNPs associated with the lipid trait identified from a prior meta-analysis (threshold P < 2 × 10(-6)); and the second a restricted score, filtered to remove any SNPs also associated with either of the other two lipid traits at P ≤ 0.01. Mendelian randomization meta-analyses were conducted in 17 studies including 62,199 participants and 12,099 CHD events. Both the unrestricted and restricted allele scores for LDL-C (42 and 19 SNPs, respectively) associated with CHD. For HDL-C, the unrestricted allele score (48 SNPs) was associated with CHD (OR: 0.53; 95% CI: 0.40, 0.70), per 1 mmol/L higher HDL-C, but neither the restricted allele score (19 SNPs; OR: 0.91; 95% CI: 0.42, 1.98) nor the unrestricted HDL-C allele score adjusted for triglycerides, LDL-C, or statin use (OR: 0.81; 95% CI: 0.44, 1.46) showed a robust association. For triglycerides, the unrestricted allele score (67 SNPs) and the restricted allele score (27 SNPs) were both associated with CHD (OR: 1.62; 95% CI: 1.24, 2.11 and 1.61; 95% CI: 1.00, 2.59, respectively) per 1-log unit increment. However, the unrestricted triglyceride score adjusted for HDL-C, LDL-C, and statin use gave an OR for CHD of 1.01 (95% CI: 0.59, 1.75). CONCLUSION: The genetic findings support a causal effect of triglycerides on CHD risk, but a causal role for HDL-C, though possible, remains less certain.
Keywords: Case-Control Studies; Cholesterol, HDL; Coronary Artery Disease; Female; Gene Frequency; Genotype; Genotyping Techniques; Humans; Male; Mendelian Randomization Analysis; Middle Aged; Polymorphism, Single Nucleotide; Risk Assessment; Triglycerides

Meta-analysis of 65,734 individuals identifies TSPAN15 and SLC44A2 as two susceptibility loci for venous thromboembolism. - Germain, Marine; Chasman, Daniel I; de Haan, Hugoline; Tang, Weihong; Lindström, Sara; Weng, Lu-Chen; de Andrade, Mariza; de Visser, Marieke C H; Wiggins, Kerri L; Suchon, Pierre; Saut, Noémie; Smadja, David M; et al. (Am J Hum Genet, 2015)
Venous thromboembolism (VTE), the third leading cause of cardiovascular mortality, is a complex thrombotic disorder with environmental and genetic determinants. Although several genetic variants have been found associated with VTE, they explain a minor proportion of VTE risk in cases. We undertook a meta-analysis of genome-wide association studies (GWASs) to identify additional VTE susceptibility genes. Twelve GWASs totaling 7,507 VTE case subjects and 52,632 control subjects formed our discovery stage where 6,751,884 SNPs were tested for association with VTE. Nine loci reached the genome-wide significance level of 5 × 10(-8) including six already known to associate with VTE (ABO, F2, F5, F11, FGG, and PROCR) and three unsuspected loci. SNPs mapping to these latter were selected for replication in three independent case-control studies totaling 3,009 VTE-affected individuals and 2,586 control subjects. This strategy led to the identification and replication of two VTE-associated loci, TSPAN15 and SLC44A2, with lead risk alleles associated with odds ratio for disease of 1.31 (p = 1.67 × 10(-16)) and 1.21 (p = 2.75 × 10(-15)), respectively. The lead SNP at the TSPAN15 locus is the intronic rs78707713 and the lead SLC44A2 SNP is the non-synonymous rs2288904 previously shown to associate with transfusion-related acute lung injury. We further showed that these two variants did not associate with known hemostatic plasma markers. TSPAN15 and SLC44A2 do not belong to conventional pathways for thrombosis and have not been associated to other cardiovascular diseases nor related quantitative biomarkers. Our findings uncovered unexpected actors of VTE etiology and pave the way for novel mechanistic concepts of VTE pathophysiology.
Keywords: Genetic Predisposition to Disease; Genome-Wide Association Study; Genotype; Humans; Membrane Glycoproteins; Membrane Transport Proteins; Odds Ratio; Tetraspanins; Venous Thromboembolism

Meta-Analysis of Genome-Wide Association Studies Identifies Genetic Risk Factors for Stroke in African Americans. - Carty, Cara L; Keene, Keith L; Cheng, Yu-Ching; Meschia, James F; Chen, Wei-Min; Nalls, Mike; Bis, Joshua C; Kittner, Steven J; Rich, Stephen S; Tajuddin, Salman; Zonderman, Alan B; Evans, Michele K; et al. (Stroke, 2015)
BACKGROUND AND PURPOSE: The majority of genome-wide association studies (GWAS) of stroke have focused on European-ancestry populations; however, none has been conducted in African Americans, despite the disproportionately high burden of stroke in this population. The Consortium of Minority Population Genome-Wide Association Studies of Stroke (COMPASS) was established to identify stroke susceptibility loci in minority populations. METHODS: Using METAL, we conducted meta-analyses of GWAS in 14 746 African Americans (1365 ischemic and 1592 total stroke cases) from COMPASS, and tested genetic variants with P<10(-6) for validation in METASTROKE, a consortium of ischemic stroke genetic studies in European-ancestry populations. We also evaluated stroke loci previously identified in European-ancestry populations. RESULTS: The 15q21.3 locus linked with lipid levels and hypertension was associated with total stroke (rs4471613; P=3.9×10(-8)) in African Americans. Nominal associations (P<10(-6)) for total or ischemic stroke were observed for 18 variants in or near genes implicated in cell cycle/mRNA presplicing (PTPRG, CDC5L), platelet function (HPS4), blood-brain barrier permeability (CLDN17), immune response (ELTD1, WDFY4, and IL1F10-IL1RN), and histone modification (HDAC9). Two of these loci achieved nominal significance in METASTROKE: 5q35.2 (P=0.03), and 1p31.1 (P=0.018). Four of 7 previously reported ischemic stroke loci (PITX2, HDAC9, CDKN2A/CDKN2B, and ZFHX3) were nominally associated (P<0.05) with stroke in COMPASS. CONCLUSIONS: We identified a novel genetic variant associated with total stroke in African Americans and found that ischemic stroke loci identified in European-ancestry populations may also be relevant for African Americans. Our findings support investigation of diverse populations to identify and characterize genetic risk factors, and the importance of shared genetic risk across populations.
Keywords: African Americans; Case-Control Studies; Cohort Studies; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Polymorphism, Single Nucleotide; Risk Factors; Stroke

A Meta-analysis of the Association of Estimated GFR, Albuminuria, Diabetes Mellitus, and Hypertension With Acute Kidney Injury. - James, Matthew T; Grams, Morgan E; Woodward, Mark; Elley, C Raina; Green, Jamie A; Wheeler, David C; de Jong, Paul; Gansevoort, Ron T; Levey, Andrew S; Warnock, David G; Sarnak, Mark J (Am J Kidney Dis, 2015)
BACKGROUND: Diabetes mellitus and hypertension are risk factors for acute kidney injury (AKI). Whether estimated glomerular filtration rate (eGFR) and urine albumin-creatinine ratio (ACR) remain risk factors for AKI in the presence and absence of these conditions is uncertain. STUDY DESIGN: Meta-analysis of cohort studies. SETTING & POPULATION: 8 general-population (1,285,045 participants) and 5 chronic kidney disease (CKD; 79,519 participants) cohorts. SELECTION CRITERIA FOR STUDIES: Cohorts participating in the CKD Prognosis Consortium. PREDICTORS: Diabetes and hypertension status, eGFR by the 2009 CKD Epidemiology Collaboration creatinine equation, urine ACR, and interactions. OUTCOME: Hospitalization with AKI, using Cox proportional hazards models to estimate HRs of AKI and random-effects meta-analysis to pool results. RESULTS: During a mean follow-up of 4 years, there were 16,480 episodes of AKI in the general-population and 2,087 episodes in the CKD cohorts. Low eGFRs and high ACRs were associated with higher risks of AKI in individuals with or without diabetes and with or without hypertension. When compared to a common reference of eGFR of 80mL/min/1.73m(2) in nondiabetic patients, HRs for AKI were generally higher in diabetic patients at any level of eGFR. The same was true for diabetic patients at all levels of ACR compared with nondiabetic patients. The risk gradient for AKI with lower eGFRs was greater in those without diabetes than with diabetes, but similar with higher ACRs in those without versus with diabetes. Those with hypertension had a higher risk of AKI at eGFRs>60mL/min/1.73m(2) than those without hypertension. However, risk gradients for AKI with both lower eGFRs and higher ACRs were greater for those without than with hypertension. LIMITATIONS: AKI identified by diagnostic code. CONCLUSIONS: Lower eGFRs and higher ACRs are associated with higher risks of AKI among individuals with or without either diabetes or hypertension.
Keywords: Acute Kidney Injury; Adult; Aged; Comorbidity; Diabetes Mellitus; Disease Progression; Female; Glomerular Filtration Rate; Humans; Hypertension; Incidence; Kidney Failure, Chronic; Male; Middle Aged; Prognosis; Renal Insufficiency, Chronic

Multiethnic genome-wide association study of cerebral white matter hyperintensities on MRI. - Verhaaren, Benjamin F J; Debette, Stephanie; Bis, Joshua C; Smith, Jennifer A; Ikram, M Kamran; Adams, Hieab H; Beecham, Ashley H; Rajan, Kumar B; Lopez, Lorna M; Barral, Sandra; van Buchem, Mark A; van der Grond, Jeroen; et al. (Circ Cardiovasc Genet, 2015)
BACKGROUND: The burden of cerebral white matter hyperintensities (WMH) is associated with an increased risk of stroke, dementia, and death. WMH are highly heritable, but their genetic underpinnings are incompletely characterized. To identify novel genetic variants influencing WMH burden, we conducted a meta-analysis of multiethnic genome-wide association studies. METHODS AND RESULTS: We included 21 079 middle-aged to elderly individuals from 29 population-based cohorts, who were free of dementia and stroke and were of European (n=17 936), African (n=1943), Hispanic (n=795), and Asian (n=405) descent. WMH burden was quantified on MRI either by a validated automated segmentation method or a validated visual grading scale. Genotype data in each study were imputed to the 1000 Genomes reference. Within each ethnic group, we investigated the relationship between each single-nucleotide polymorphism and WMH burden using a linear regression model adjusted for age, sex, intracranial volume, and principal components of ancestry. A meta-analysis was conducted for each ethnicity separately and for the combined sample. In the European descent samples, we confirmed a previously known locus on chr17q25 (P=2.7×10(-19)) and identified novel loci on chr10q24 (P=1.6×10(-9)) and chr2p21 (P=4.4×10(-8)). In the multiethnic meta-analysis, we identified 2 additional loci, on chr1q22 (P=2.0×10(-8)) and chr2p16 (P=1.5×10(-8)). The novel loci contained genes that have been implicated in Alzheimer disease (chr2p21 and chr10q24), intracerebral hemorrhage (chr1q22), neuroinflammatory diseases (chr2p21), and glioma (chr10q24 and chr2p16). CONCLUSIONS: We identified 4 novel genetic loci that implicate inflammatory and glial proliferative pathways in the development of WMH in addition to previously proposed ischemic mechanisms.
Keywords: Aged; Aged, 80 and over; Chromosomes, Human; Continental Population Groups; Female; Genetic Loci; Genome-Wide Association Study; Humans; Male; Meta-Analysis as Topic; Middle Aged; Models, Genetic; Stroke; White Matter

Novel loci associated with usual sleep duration: the CHARGE Consortium Genome-Wide Association Study. - Gottlieb, D J; Hek, K; Chen, T-H; Watson, N F; Eiriksdottir, G; Byrne, E M; Cornelis, M; Warby, S C; Bandinelli, S; Cherkas, L; Evans, D S; Grabe, H J; et al. (Mol Psychiatry, 2015)
Usual sleep duration is a heritable trait correlated with psychiatric morbidity, cardiometabolic disease and mortality, although little is known about the genetic variants influencing this trait. A genome-wide association study (GWAS) of usual sleep duration was conducted using 18 population-based cohorts totaling 47 180 individuals of European ancestry. Genome-wide significant association was identified at two loci. The strongest is located on chromosome 2, in an intergenic region 35- to 80-kb upstream from the thyroid-specific transcription factor PAX8 (lowest P=1.1 × 10(-9)). This finding was replicated in an African-American sample of 4771 individuals (lowest P=9.3 × 10(-4)). The strongest combined association was at rs1823125 (P=1.5 × 10(-10), minor allele frequency 0.26 in the discovery sample, 0.12 in the replication sample), with each copy of the minor allele associated with a sleep duration 3.1 min longer per night. The alleles associated with longer sleep duration were associated in previous GWAS with a more favorable metabolic profile and a lower risk of attention deficit hyperactivity disorder. Understanding the mechanisms underlying these associations may help elucidate biological mechanisms influencing sleep duration and its association with psychiatric, metabolic and cardiovascular disease.
Keywords: Adult; African Americans; Aged; Dyssomnias; European Continental Ancestry Group; Female; Genetic Association Studies; Genome-Wide Association Study; Humans; Male; Middle Aged; Polymorphism, Single Nucleotide; Self Report; Sleep

Plasma Levels of Soluble Interleukin-2 Receptor α: Associations With Clinical Cardiovascular Events and Genome-Wide Association Scan. - Durda, Peter; Sabourin, Jeremy; Lange, Ethan M; Nalls, Mike A; Mychaleckyj, Josyf C; Jenny, Nancy Swords; Li, Jin; Walston, Jeremy; Harris, Tamara B; Psaty, Bruce M; Valdar, William; Liu, Yongmei; et al. (Arterioscler Thromb Vasc Biol, 2015)
OBJECTIVE: Interleukin (IL) -2 receptor subunit α regulates lymphocyte activation, which plays an important role in atherosclerosis. Associations between soluble IL-2Rα (sIL-2Rα) and cardiovascular disease (CVD) have not been widely studied and little is known about the genetic determinants of sIL-2Rα levels. APPROACH AND RESULTS: We measured baseline levels of sIL-2Rα in 4408 European American (EA) and 766 African American (AA) adults from the Cardiovascular Health Study (CHS) and examined associations with baseline CVD risk factors, subclinical CVD, and incident CVD events. We also performed a genome-wide association study for sIL-2Rα in CHS (2964 EAs and 683 AAs) and further combined CHS EA results with those from two other EA cohorts in a meta-analysis (n=4464 EAs). In age, sex- and race- adjusted models, sIL-2Rα was positively associated with current smoking, type 2 diabetes mellitus, hypertension, insulin, waist circumference, C-reactive protein, IL-6, fibrinogen, internal carotid wall thickness, all-cause mortality, CVD mortality, and incident CVD, stroke, and heart failure. When adjusted for baseline CVD risk factors and subclinical CVD, associations with all-cause mortality, CVD mortality, and heart failure remained significant in both EAs and AAs. In the EA genome-wide association study analysis, we observed 52 single-nucleotide polymorphisms in the chromosome 10p15-14 region, which contains IL2RA, IL15RA, and RMB17, that reached genome-wide significance (P<5×10(-8)). The most significant single-nucleotide polymorphism was rs7911500 (P=1.31×10(-75)). The EA meta-analysis results were highly consistent with CHS-only results. No single-nucleotide polymorphisms reached statistical significance in the AAs. CONCLUSIONS: These results support a role for sIL-2Rα in atherosclerosis and provide evidence for multiple-associated single-nucleotide polymorphisms at chromosome 10p15-14.
Keywords: Adult; African Americans; Age Distribution; Aged; Cardiovascular Diseases; Cohort Studies; Coronary Artery Disease; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Incidence; Interleukin-2 Receptor alpha Subunit; Kaplan-Meier Estimate; Male; Middle Aged; Polymorphism, Single Nucleotide; Proportional Hazards Models; Prospective Studies; Risk Assessment; Sex Distribution; Survival Analysis

Positive association of tomato consumption with serum urate: support for tomato consumption as an anecdotal trigger of gout flares. - Flynn, Tanya J; Cadzow, Murray; Dalbeth, Nicola; Jones, Peter B; Stamp, Lisa K; Hindmarsh, Jennie Harré; Todd, Alwyn S; Walker, Robert J; Topless, Ruth; Merriman, Tony R (BMC Musculoskelet Disord, 2015)
BACKGROUND: Gout is a consequence of an innate immune reaction to monosodium urate crystals deposited in joints. Acute gout attacks can be triggered by dietary factors that are themselves associated with serum urate levels. Tomato consumption is an anecdotal trigger of gout flares. This study aimed to measure the frequency of tomato consumption as a self-reported trigger of gout attacks in a large New Zealand sample set, and to test the hypothesis that tomato consumption is associated with serum urate levels. METHODS: Two thousand fifty one New Zealanders (of Māori, Pacific Island, European or other ancestry) with clinically-ascertained gout were asked about gout trigger foods. European individuals from the Atherosclerosis Risk In Communities (ARIC; n = 7517) Study, Cardiovascular Health Study (CHS; n = 2151) and Framingham Heart Study (FHS; n = 3052) were used to test, in multivariate-adjusted analyses, for association between serum urate and tomato intake. RESULTS: Seventy one percent of people with gout reported having ≥1 gout trigger food. Of these 20% specifically mentioned tomatoes, the 4(th) most commonly reported trigger food. There was association between tomato intake and serum urate levels in the ARIC, CHS and FHS combined cohort (β = 0.66 μmolL(-1) increase in serum urate per additional serve per week; P = 0.006) - evident in both sexes (men: β = 0.84 μmolL(-1), P = 0.035; women: β = 0.59 μmolL (-1), P = 0.041). CONCLUSIONS: While our descriptive and observational data are unable to support the claim that tomato consumption is a trigger of gout attacks, the positive association between tomato consumption and serum urate levels suggests that the self-reporting of tomatoes as a dietary trigger by people with gout has a biological basis.
Keywords: Adolescent; Adult; Aged; European Continental Ancestry Group; Female; Gout; Humans; Hyperuricemia; Lycopersicon esculentum; Male; Middle Aged; New Zealand; Oceanic Ancestry Group; Surveys and Questionnaires; Uric Acid; Young Adult

Prospective association of fatty acids in the de novo lipogenesis pathway with risk of type 2 diabetes: the Cardiovascular Health Study. - Ma, Wenjie; Wu, Jason H Y; Wang, Qianyi; Lemaitre, Rozenn N; Mukamal, Kenneth J; Djoussé, Luc; King, Irena B; Song, Xiaoling; Biggs, Mary L; Delaney, Joseph A; Kizer, Jorge R; Siscovick, David S; et al. (Am J Clin Nutr, 2015)
BACKGROUND: Experimental evidence suggests that hepatic de novo lipogenesis (DNL) affects insulin homeostasis via synthesis of saturated fatty acids (SFAs) and monounsaturated fatty acids (MUFAs). Few prospective studies have used fatty acid biomarkers to assess associations with type 2 diabetes. OBJECTIVES: We investigated associations of major circulating SFAs [palmitic acid (16:0) and stearic acid (18:0)] and MUFA [oleic acid (18:1n-9)] in the DNL pathway with metabolic risk factors and incident diabetes in community-based older U.S. adults in the Cardiovascular Health Study. We secondarily assessed other DNL fatty acid biomarkers [myristic acid (14:0), palmitoleic acid (16:1n-7), 7-hexadecenoic acid (16:1n-9), and vaccenic acid (18:1n-7)] and estimated dietary SFAs and MUFAs. DESIGN: In 3004 participants free of diabetes, plasma phospholipid fatty acids were measured in 1992, and incident diabetes was identified by medication use and blood glucose. Usual diets were assessed by using repeated food-frequency questionnaires. Multivariable linear and Cox regression were used to assess associations with metabolic risk factors and incident diabetes, respectively. RESULTS: At baseline, circulating palmitic acid and stearic acid were positively associated with adiposity, triglycerides, inflammation biomarkers, and insulin resistance (P-trend < 0.01 each), whereas oleic acid showed generally beneficial associations (P-trend < 0.001 each). During 30,763 person-years, 297 incident diabetes cases occurred. With adjustment for demographics and lifestyle, palmitic acid (extreme-quintile HR: 1.89; 95% CI: 1.27, 2.83; P-trend = 0.001) and stearic acid (HR: 1.62; 95% CI: 1.09, 2.41; P-trend = 0.006) were associated with higher diabetes risk, whereas oleic acid was not significantly associated. In secondary analyses, vaccenic acid was inversely associated with diabetes (HR: 0.56; 95% CI: 0.38, 0.83; P-trend = 0.005). Other fatty acid biomarkers and estimated dietary SFAs or MUFAs were not significantly associated with incident diabetes. CONCLUSIONS: In this large prospective cohort, circulating palmitic acid and stearic acid were associated with higher diabetes risk, and vaccenic acid was associated with lower diabetes risk. These results indicate a need for additional investigation of biological mechanisms linking specific fatty acids in the DNL pathway to the pathogenesis of diabetes.
Keywords: Aged; Biomarkers; Cohort Studies; Cross-Sectional Studies; Diabetes Mellitus, Type 2; Female; Follow-Up Studies; Humans; Incidence; Lipogenesis; Liver; Male; Palmitic Acid; Phospholipids; Prevalence; Proportional Hazards Models; Risk Factors; Stearic Acids; United States; Up-Regulation

Rare and Coding Region Genetic Variants Associated With Risk of Ischemic Stroke: The NHLBI Exome Sequence Project. - Auer, Paul L; Nalls, Mike; Meschia, James F; Worrall, Bradford B; Longstreth, W T; Seshadri, Sudha; Kooperberg, Charles; Burger, Kathleen M; Carlson, Christopher S; Carty, Cara L; Chen, Wei-Min; Cupples, L Adrienne; et al. (JAMA Neurol, 2015)
IMPORTANCE: Stroke is the second leading cause of death and the third leading cause of years of life lost. Genetic factors contribute to stroke prevalence, and candidate gene and genome-wide association studies (GWAS) have identified variants associated with ischemic stroke risk. These variants often have small effects without obvious biological significance. Exome sequencing may discover predicted protein-altering variants with a potentially large effect on ischemic stroke risk. OBJECTIVE: To investigate the contribution of rare and common genetic variants to ischemic stroke risk by targeting the protein-coding regions of the human genome. DESIGN, SETTING, AND PARTICIPANTS: The National Heart, Lung, and Blood Institute (NHLBI) Exome Sequencing Project (ESP) analyzed approximately 6000 participants from numerous cohorts of European and African ancestry. For discovery, 365 cases of ischemic stroke (small-vessel and large-vessel subtypes) and 809 European ancestry controls were sequenced; for replication, 47 affected sibpairs concordant for stroke subtype and an African American case-control series were sequenced, with 1672 cases and 4509 European ancestry controls genotyped. The ESP's exome sequencing and genotyping started on January 1, 2010, and continued through June 30, 2012. Analyses were conducted on the full data set between July 12, 2012, and July 13, 2013. MAIN OUTCOMES AND MEASURES: Discovery of new variants or genes contributing to ischemic stroke risk and subtype (primary analysis) and determination of support for protein-coding variants contributing to risk in previously published candidate genes (secondary analysis). RESULTS: We identified 2 novel genes associated with an increased risk of ischemic stroke: a protein-coding variant in PDE4DIP (rs1778155; odds ratio, 2.15; P = 2.63 × 10(-8)) with an intracellular signal transduction mechanism and in ACOT4 (rs35724886; odds ratio, 2.04; P = 1.24 × 10(-7)) with a fatty acid metabolism; confirmation of PDE4DIP was observed in affected sibpair families with large-vessel stroke subtype and in African Americans. Replication of protein-coding variants in candidate genes was observed for 2 previously reported GWAS associations: ZFHX3 (cardioembolic stroke) and ABCA1 (large-vessel stroke). CONCLUSIONS AND RELEVANCE: Exome sequencing discovered 2 novel genes and mechanisms, PDE4DIP and ACOT4, associated with increased risk for ischemic stroke. In addition, ZFHX3 and ABCA1 were discovered to have protein-coding variants associated with ischemic stroke. These results suggest that genetic variation in novel pathways contributes to ischemic stroke risk and serves as a target for prediction, prevention, and therapy.
Keywords: Aged; Brain Ischemia; Exome; Female; Genetic Predisposition to Disease; Genetic Variation; Genome-Wide Association Study; Humans; Male; Middle Aged; Muscle Proteins; National Heart, Lung, and Blood Institute (U.S.); Nuclear Proteins; Open Reading Frames; Palmitoyl-CoA Hydrolase; Stroke; United States

Rare and low-frequency variants and their association with plasma levels of fibrinogen, FVII, FVIII, and vWF. - Huffman, Jennifer E; de Vries, Paul S; Morrison, Alanna C; Sabater-Lleal, Maria; Kacprowski, Tim; Auer, Paul L; Brody, Jennifer A; Chasman, Daniel I; Chen, Ming-Huei; Guo, Xiuqing; Lin, Li-An; Marioni, Riccardo E; et al. (Blood, 2015)
Fibrinogen, coagulation factor VII (FVII), and factor VIII (FVIII) and its carrier von Willebrand factor (vWF) play key roles in hemostasis. Previously identified common variants explain only a small fraction of the trait heritabilities, and additional variations may be explained by associations with rarer variants with larger effects. The aim of this study was to identify low-frequency (minor allele frequency [MAF] ≥0.01 and <0.05) and rare (MAF <0.01) variants that influence plasma concentrations of these 4 hemostatic factors by meta-analyzing exome chip data from up to 76,000 participants of 4 ancestries. We identified 12 novel associations of low-frequency (n = 2) and rare (n = 10) variants across the fibrinogen, FVII, FVIII, and vWF traits that were independent of previously identified associations. Novel loci were found within previously reported genes and had effect sizes much larger than and independent of previously identified common variants. In addition, associations at KCNT1, HID1, and KATNB1 identified new candidate genes related to hemostasis for follow-up replication and functional genomic analysis. Newly identified low-frequency and rare-variant associations accounted for modest amounts of trait variance and therefore are unlikely to increase predicted trait heritability but provide new information for understanding individual variation in hemostasis pathways.
Keywords: Cohort Studies; Factor VII; Factor VIII; Fibrinogen; Gene Frequency; Genetic Association Studies; Genetic Variation; Humans; Nerve Tissue Proteins; Polymorphism, Single Nucleotide; Potassium Channels; von Willebrand Factor

Serial measures of cardiac troponin T levels by a highly sensitive assay and incident atrial fibrillation in a prospective cohort of ambulatory older adults. - Hussein, Ayman A; Bartz, Traci M; Gottdiener, John S; Sotoodehnia, Nona; Heckbert, Susan R; Lloyd-Jones, Donald; Kizer, Jorge R; Christenson, Robert; Wazni, Oussama; DeFilippi, Christopher (Heart Rhythm, 2015)
BACKGROUND: Various mechanisms in cardiac remodeling related to atrial fibrillation (AF) lead to elevated circulating cardiac troponin levels, but little is known about such elevations upstream to AF onset. OBJECTIVE: The purpose of this study was to study the association between circulating troponin levels as assessed by a highly sensitive cardiac troponin T (hs-cTnT) assay and incident atrial fibrillation (AF). METHODS: In a large prospective cohort of ambulatory older adults [the Cardiovascular Health Study (CHS)], hs-cTnT levels were measured in sera that were collected at enrollment from 4262 participants without AF (2871 with follow-up measurements). Incident AF was identified by electrocardiograms during CHS visits, hospital discharge diagnoses, and Medicare files, including outpatient and physician claims diagnoses. RESULTS: Over median follow-up of 11.2 years (interquartile range 6.1-16.5), 1363 participants (32.0%) developed AF. Higher baseline levels of hs-cTnT were associated with incident AF in covariate-adjusted analyses accounting for demographics, traditional risk factors, and incident heart failure in time-dependent analyzes (hazard ratio for 3rd tertile vs undetectable 1.75, 95% confidence interval 1.48-2.08). This association was statistically significant in analyses that additionally adjusted for biomarkers of inflammation and hemodynamic strain (hazard ratio for 3rd tertile vs undetectable 1.38, 95% confidence interval 1.16-1.65). Significant associations were also found when hs-cTnT levels were treated as a continuous variable and when examining change from baseline of hs-cTnT levels and incident AF. CONCLUSION: The findings show a significant association of circulating troponin levels in ambulatory older adults with incident AF beyond that of traditional risk factors, incident heart failure, and biomarkers of inflammation and hemodynamic strain.
Keywords: Aged; Atrial Fibrillation; Biomarkers; Electrocardiography; Female; Heart Failure; Humans; Incidence; Longitudinal Studies; Male; Outpatients; Risk Assessment; Risk Factors; Statistics as Topic; Troponin T; United States

Serum urate levels and the risk of hip fractures: data from the Cardiovascular Health Study. - Mehta, Tapan; Bůzková, Petra; Sarnak, Mark J; Chonchol, Michel; Cauley, Jane A; Wallace, Erin; Fink, Howard A; Robbins, John; Jalal, Diana (Metabolism, 2015)
PURPOSE: Uric acid inhibits vitamin D activation experimentally and higher serum urate levels are associated with higher parathyroid hormone levels in humans suggesting a link between uric acid and bone health. We hypothesized that hyperuricemia may increase the risk of fractures in older adults. METHODS: 1963 men and 2729 women ≥65 years of age who participated in the Cardiovascular Health Study and had baseline serum urate levels were included in the study. The primary outcome was incident hip fracture, assessed prospectively through June, 2008 by inpatient and outpatient records. The analysis was stratified by sex a priori. RESULTS: There was a U-shaped relationship between serum urate levels and hip fractures in men. Men in the lowest and the highest urate quartiles (<4.88 and ≥6.88 mg/dL respectively) had a significantly higher rate of fractures in unadjusted analysis. However, upon multivariate adjustment, only the HR for hip fracture in highest quartile versus the reference remained significant (HR 1.9; 95% C.I. 1.1, 3.1; p value 0.02). High serum urate levels were not associated with hip fractures in women. CONCLUSION: In this large prospective cohort of community-dwelling older adults, increased serum urate levels were associated with an increased risk of hip fractures in men. Further studies are needed to confirm these findings and to understand the mechanisms that underlie them.
Keywords: Aged; Aged, 80 and over; Body Mass Index; Cohort Studies; Estrogen Replacement Therapy; Female; Health Surveys; Hip Fractures; Humans; Kaplan-Meier Estimate; Male; Prospective Studies; Risk; Sex Factors; United States; Uric Acid

Sex, Race, and Age Differences in Observed Years of Life, Healthy Life, and Able Life among Older Adults in The Cardiovascular Health Study. - Thielke, Stephen M; Diehr, Paula H; Yee, Laura M; Arnold, Alice M; Quiñones, Ana R; Whitson, Heather E; Jacob, Mini E; Newman, Anne B (J Pers Med, 2015)
OBJECTIVE: Longevity fails to account for health and functional status during aging. We sought to quantify differences in years of total life, years of healthy life, and years of able life among groups defined by age, sex, and race. DESIGN: Primary analysis of a cohort study. SETTING: 18 years of annual evaluations in four U.S. communities. PARTICIPANTS: 5888 men and women aged 65 and older. MEASUREMENTS: Years of life were calculated as the time from enrollment to death or 18 years. Years of total, healthy, and able life were determined from self-report during annual or semi-annual contacts. Cumulative years were summed across each of the age and sex groups. RESULTS: White women had the best outcomes for all three measures, followed by white men, non-white women, and non-white men. For example, at the mean age of 73, a white female participant could expect 12.9 years of life, 8.9 of healthy life and 9.5 of able life, while a non-white female could expect 12.6, 7.0, and 8.0 years, respectively. A white male could expect 11.2, 8.1, and 8.9 years of life, healthy life, and able life, and a non-white male 10.3, 6.2, and 7.9 years. Regardless of starting age, individuals of the same race and sex groups spent similar amounts (not proportions) of time in an unhealthy or unable state. CONCLUSION: Gender had a greater effect on longevity than did race, but race had a greater effect on years spent healthy or able. The mean number of years spent in an unable or sick state was surprisingly independent of the lifespan.

Shared genetic basis for migraine and ischemic stroke: A genome-wide analysis of common variants. - Malik, Rainer; Freilinger, Tobias; Winsvold, Bendik S; Anttila, Verneri; Vander Heiden, Jason; Traylor, Matthew; de Vries, Boukje; Holliday, Elizabeth G; Terwindt, Gisela M; Sturm, Jonathan; Bis, Joshua C; Hopewell, Jemma C; et al. (Neurology, 2015)
OBJECTIVE: To quantify genetic overlap between migraine and ischemic stroke (IS) with respect to common genetic variation. METHODS: We applied 4 different approaches to large-scale meta-analyses of genome-wide data on migraine (23,285 cases and 95,425 controls) and IS (12,389 cases and 62,004 controls). First, we queried known genome-wide significant loci for both disorders, looking for potential overlap of signals. We then analyzed the overall shared genetic load using polygenic scores and estimated the genetic correlation between disease subtypes using data derived from these models. We further interrogated genomic regions of shared risk using analysis of covariance patterns between the 2 phenotypes using cross-phenotype spatial mapping. RESULTS: We found substantial genetic overlap between migraine and IS using all 4 approaches. Migraine without aura (MO) showed much stronger overlap with IS and its subtypes than migraine with aura (MA). The strongest overlap existed between MO and large artery stroke (LAS; p = 6.4 × 10(-28) for the LAS polygenic score in MO) and between MO and cardioembolic stroke (CE; p = 2.7 × 10(-20) for the CE score in MO). CONCLUSIONS: Our findings indicate shared genetic susceptibility to migraine and IS, with a particularly strong overlap between MO and both LAS and CE pointing towards shared mechanisms. Our observations on MA are consistent with a limited role of common genetic variants in this subtype.
Keywords: Brain Ischemia; Genome-Wide Association Study; Humans; Migraine with Aura; Migraine without Aura; Stroke

Subclinical Hypothyroidism and the Risk of Stroke Events and Fatal Stroke: An Individual Participant Data Analysis. - Chaker, Layal; Baumgartner, Christine; den Elzen, Wendy P J; Ikram, M Arfan; Blum, Manuel R; Collet, Tinh-Hai; Bakker, Stephan J L; Dehghan, Abbas; Drechsler, Christiane; Luben, Robert N; Hofman, Albert; Portegies, Marileen L P; et al. (J Clin Endocrinol Metab, 2015)
OBJECTIVE: The objective was to determine the risk of stroke associated with subclinical hypothyroidism. DATA SOURCES AND STUDY SELECTION: Published prospective cohort studies were identified through a systematic search through November 2013 without restrictions in several databases. Unpublished studies were identified through the Thyroid Studies Collaboration. We collected individual participant data on thyroid function and stroke outcome. Euthyroidism was defined as TSH levels of 0.45-4.49 mIU/L, and subclinical hypothyroidism was defined as TSH levels of 4.5-19.9 mIU/L with normal T4 levels. DATA EXTRACTION AND SYNTHESIS: We collected individual participant data on 47 573 adults (3451 subclinical hypothyroidism) from 17 cohorts and followed up from 1972-2014 (489 192 person-years). Age- and sex-adjusted pooled hazard ratios (HRs) for participants with subclinical hypothyroidism compared to euthyroidism were 1.05 (95% confidence interval [CI], 0.91-1.21) for stroke events (combined fatal and nonfatal stroke) and 1.07 (95% CI, 0.80-1.42) for fatal stroke. Stratified by age, the HR for stroke events was 3.32 (95% CI, 1.25-8.80) for individuals aged 18-49 years. There was an increased risk of fatal stroke in the age groups 18-49 and 50-64 years, with a HR of 4.22 (95% CI, 1.08-16.55) and 2.86 (95% CI, 1.31-6.26), respectively (p trend 0.04). We found no increased risk for those 65-79 years old (HR, 1.00; 95% CI, 0.86-1.18) or ≥ 80 years old (HR, 1.31; 95% CI, 0.79-2.18). There was a pattern of increased risk of fatal stroke with higher TSH concentrations. CONCLUSIONS: Although no overall effect of subclinical hypothyroidism on stroke could be demonstrated, an increased risk in subjects younger than 65 years and those with higher TSH concentrations was observed.
Keywords: Adult; Asymptomatic Diseases; Female; Humans; Hypothyroidism; Incidence; Male; Risk Factors; Stroke; Thyrotropin

Subclinical thyroid dysfunction and fracture risk: a meta-analysis. - Blum, Manuel R; Bauer, Douglas C; Collet, Tinh-Hai; Fink, Howard A; Cappola, Anne R; da Costa, Bruno R; Wirth, Christina D; Peeters, Robin P; Asvold, Bjørn O; den Elzen, Wendy P J; Luben, Robert N; Imaizumi, Misa; et al. (JAMA, 2015)
IMPORTANCE: Associations between subclinical thyroid dysfunction and fractures are unclear and clinical trials are lacking. OBJECTIVE: To assess the association of subclinical thyroid dysfunction with hip, nonspine, spine, or any fractures. DATA SOURCES AND STUDY SELECTION: The databases of MEDLINE and EMBASE (inception to March 26, 2015) were searched without language restrictions for prospective cohort studies with thyroid function data and subsequent fractures. DATA EXTRACTION: Individual participant data were obtained from 13 prospective cohorts in the United States, Europe, Australia, and Japan. Levels of thyroid function were defined as euthyroidism (thyroid-stimulating hormone [TSH], 0.45-4.49 mIU/L), subclinical hyperthyroidism (TSH <0.45 mIU/L), and subclinical hypothyroidism (TSH ≥4.50-19.99 mIU/L) with normal thyroxine concentrations. MAIN OUTCOME AND MEASURES: The primary outcome was hip fracture. Any fractures, nonspine fractures, and clinical spine fractures were secondary outcomes. RESULTS: Among 70,298 participants, 4092 (5.8%) had subclinical hypothyroidism and 2219 (3.2%) had subclinical hyperthyroidism. During 762,401 person-years of follow-up, hip fracture occurred in 2975 participants (4.6%; 12 studies), any fracture in 2528 participants (9.0%; 8 studies), nonspine fracture in 2018 participants (8.4%; 8 studies), and spine fracture in 296 participants (1.3%; 6 studies). In age- and sex-adjusted analyses, the hazard ratio (HR) for subclinical hyperthyroidism vs euthyroidism was 1.36 for hip fracture (95% CI, 1.13-1.64; 146 events in 2082 participants vs 2534 in 56,471); for any fracture, HR was 1.28 (95% CI, 1.06-1.53; 121 events in 888 participants vs 2203 in 25,901); for nonspine fracture, HR was 1.16 (95% CI, 0.95-1.41; 107 events in 946 participants vs 1745 in 21,722); and for spine fracture, HR was 1.51 (95% CI, 0.93-2.45; 17 events in 732 participants vs 255 in 20,328). Lower TSH was associated with higher fracture rates: for TSH of less than 0.10 mIU/L, HR was 1.61 for hip fracture (95% CI, 1.21-2.15; 47 events in 510 participants); for any fracture, HR was 1.98 (95% CI, 1.41-2.78; 44 events in 212 participants); for nonspine fracture, HR was 1.61 (95% CI, 0.96-2.71; 32 events in 185 participants); and for spine fracture, HR was 3.57 (95% CI, 1.88-6.78; 8 events in 162 participants). Risks were similar after adjustment for other fracture risk factors. Endogenous subclinical hyperthyroidism (excluding thyroid medication users) was associated with HRs of 1.52 (95% CI, 1.19-1.93) for hip fracture, 1.42 (95% CI, 1.16-1.74) for any fracture, and 1.74 (95% CI, 1.01-2.99) for spine fracture. No association was found between subclinical hypothyroidism and fracture risk. CONCLUSIONS AND RELEVANCE: Subclinical hyperthyroidism was associated with an increased risk of hip and other fractures, particularly among those with TSH levels of less than 0.10 mIU/L and those with endogenous subclinical hyperthyroidism. Further study is needed to determine whether treating subclinical hyperthyroidism can prevent fractures.
Keywords: Adolescent; Adult; Aged; Aged, 80 and over; Female; Fractures, Bone; Hip Fractures; Humans; Hyperthyroidism; Hypothyroidism; Male; Middle Aged; Risk Factors; Spinal Fractures; Thyrotropin; Young Adult

Thyroid function in the euthyroid range and adverse outcomes in older adults. - Cappola, Anne R; Arnold, Alice M; Wulczyn, Kendra; Carlson, Michelle; Robbins, John; Psaty, Bruce M (J Clin Endocrinol Metab, 2015)
CONTEXT: The appropriateness of current reference ranges for thyroid function testing in older adults has been questioned. OBJECTIVE: This study aimed to determine the relationship between thyroid function tests within the euthyroid range and adverse outcomes in older adults not taking thyroid medication. DESIGN, SETTING, AND PARTICIPANTS: US community-dwelling adults years of older (n = 2843) enrolled onto the Cardiovascular Health Study with TSH, free T4 (FT4), and total T3 concentrations in the euthyroid range. MAIN OUTCOME MEASURES: Incidence of atrial fibrillation, coronary heart disease, heart failure, hip fracture, dementia, and all-cause death were measured. RESULTS: No departures from linearity were detected. Higher TSH was negatively associated (P = .03) and higher FT4 was positively associated (P = .007) with mortality. Higher FT4 was associated with atrial fibrillation (P < .001) and heart failure (P = .004). Compared with the first quartile, individuals with TSH in the fourth quartile had a 9.6 per 1000 person-year lower incidence of dementia (P < .05) and those with FT4 in the fourth quartile had higher incidences of atrial fibrillation, coronary heart disease, heart failure, and mortality (11.0, 8.0, 7.8, and 14.3 per 1000 person-years, respectively, all P < .05). Total T3 was not associated with any outcome. CONCLUSIONS: Higher TSH and lower FT4 concentrations within the euthyroid range are associated with lower risk of multiple adverse events in older people, including mortality. This suggests tolerance for lower thyroid hormone levels in this age group. Clinical trials are needed to evaluate the risk-benefit profile of new thresholds for initiating treatment and optimal target concentrations for thyroid hormone replacement in older people.
Keywords: Aged; Aged, 80 and over; Aging; Atrial Fibrillation; Cause of Death; Coronary Disease; Dementia; Female; Heart Failure; Hip Fractures; Humans; Incidence; Male; Prognosis; Reference Values; Survival Analysis; Thyroid Function Tests; Thyroid Gland

Thyroid function within the normal range and risk of coronary heart disease: an individual participant data analysis of 14 cohorts. - Asvold, Bjørn O; Vatten, Lars J; Bjøro, Trine; Bauer, Douglas C; Bremner, Alexandra; Cappola, Anne R; Ceresini, Graziano; den Elzen, Wendy P J; Ferrucci, Luigi; Franco, Oscar H; Franklyn, Jayne A; Gussekloo, Jacobijn; et al. (JAMA Intern Med, 2015)
IMPORTANCE: Some experts suggest that serum thyrotropin levels in the upper part of the current reference range should be considered abnormal, an approach that would reclassify many individuals as having mild hypothyroidism. Health hazards associated with such thyrotropin levels are poorly documented, but conflicting evidence suggests that thyrotropin levels in the upper part of the reference range may be associated with an increased risk of coronary heart disease (CHD). OBJECTIVE: To assess the association between differences in thyroid function within the reference range and CHD risk. DESIGN, SETTING, AND PARTICIPANTS: Individual participant data analysis of 14 cohorts with baseline examinations between July 1972 and April 2002 and with median follow-up ranging from 3.3 to 20.0 years. Participants included 55,412 individuals with serum thyrotropin levels of 0.45 to 4.49 mIU/L and no previously known thyroid or cardiovascular disease at baseline. EXPOSURES: Thyroid function as expressed by serum thyrotropin levels at baseline. MAIN OUTCOMES AND MEASURES: Hazard ratios (HRs) of CHD mortality and CHD events according to thyrotropin levels after adjustment for age, sex, and smoking status. RESULTS: Among 55,412 individuals, 1813 people (3.3%) died of CHD during 643,183 person-years of follow-up. In 10 cohorts with information on both nonfatal and fatal CHD events, 4666 of 48,875 individuals (9.5%) experienced a first-time CHD event during 533,408 person-years of follow-up. For each 1-mIU/L higher thyrotropin level, the HR was 0.97 (95% CI, 0.90-1.04) for CHD mortality and 1.00 (95% CI, 0.97-1.03) for a first-time CHD event. Similarly, in analyses by categories of thyrotropin, the HRs of CHD mortality (0.94 [95% CI, 0.74-1.20]) and CHD events (0.97 [95% CI, 0.83-1.13]) were similar among participants with the highest (3.50-4.49 mIU/L) compared with the lowest (0.45-1.49 mIU/L) thyrotropin levels. Subgroup analyses by sex and age group yielded similar results. CONCLUSIONS AND RELEVANCE: Thyrotropin levels within the reference range are not associated with risk of CHD events or CHD mortality. This finding suggests that differences in thyroid function within the population reference range do not influence the risk of CHD. Increased CHD risk does not appear to be a reason for lowering the upper thyrotropin reference limit.
Keywords: Cohort Studies; Coronary Disease; Humans; Hypothyroidism; Thyrotropin

Variation in resting heart rate over 4 years and the risks of myocardial infarction and death among older adults. - Floyd, James S; Sitlani, Colleen M; Wiggins, Kerri L; Wallace, Erin; Suchy-Dicey, Astrid; Abbasi, Siddique A; Carnethon, Mercedes R; Siscovick, David S; Sotoodehnia, Nona; Heckbert, Susan R; McKnight, Barbara; Rice, Kenneth M; et al. (Heart, 2015)
OBJECTIVE: Resting heart rate (RHR) is an established predictor of myocardial infarction (MI) and mortality, but the relationship between variation in RHR over a period of several years and health outcomes is unclear. We evaluated the relationship between long-term variation in RHR and the risks of incident MI and mortality among older adults. METHODS: 1991 subjects without cardiovascular disease from the Cardiovascular Health Study were included. RHR was taken from resting ECGs at the first five annual study visits. RHR mean, trend and variation were estimated with linear regression. Subjects were followed for incident MI and death until December 2010. HRs for RHR mean, trend and variation are reported for differences of 10 bpm, 2 bpm/year and 2 bpm, respectively. RESULTS: 262 subjects had an incident MI event (13%) and 1326 died (67%) during 12 years of median follow-up. In primary analyses adjusted for cardiovascular risk factors, RHR mean (HR 1.12; 95% CI 1.05 to 1.20) and variation (HR 1.08; 95% CI 1.03 to 1.13) were associated with the risk of death while trend was not. None of the RHR variables were significantly associated with the risk of incident MI events; however, CIs were wide and the MI associations with RHR variables were not significantly different from the mortality associations. Adjusting for additional variables did not affect estimates, and there were no significant interactions with sex. CONCLUSIONS: Variation in RHR over a period of several years represents a potential predictor of long-term mortality among older persons free of cardiovascular disease.
Keywords: Aged; Aged, 80 and over; Cause of Death; Electrocardiography; Female; Follow-Up Studies; Heart Rate; Humans; Incidence; Linear Models; Male; Myocardial Infarction; Outcome Assessment (Health Care); Prognosis; Proportional Hazards Models; Prospective Studies; Rest; Risk Factors; Time; Washington

White Matter Lesion Progression: Genome-Wide Search for Genetic Influences. - Hofer, Edith; Cavalieri, Margherita; Bis, Joshua C; DeCarli, Charles; Fornage, Myriam; Sigurdsson, Sigurdur; Srikanth, Velandai; Trompet, Stella; Verhaaren, Benjamin F J; Wolf, Christiane; Yang, Qiong; Adams, Hieab H H; et al. (Stroke, 2015)
BACKGROUND AND PURPOSE: White matter lesion (WML) progression on magnetic resonance imaging is related to cognitive decline and stroke, but its determinants besides baseline WML burden are largely unknown. Here, we estimated heritability of WML progression, and sought common genetic variants associated with WML progression in elderly participants from the Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) consortium. METHODS: Heritability of WML progression was calculated in the Framingham Heart Study. The genome-wide association study included 7773 elderly participants from 10 cohorts. To assess the relative contribution of genetic factors to progression of WML, we compared in 7 cohorts risk models including demographics, vascular risk factors plus single-nucleotide polymorphisms that have been shown to be associated cross-sectionally with WML in the current and previous association studies. RESULTS: A total of 1085 subjects showed WML progression. The heritability estimate for WML progression was low at 6.5%, and no single-nucleotide polymorphisms achieved genome-wide significance (P<5×10(-8)). Four loci were suggestive (P<1×10(-5)) of an association with WML progression: 10q24.32 (rs10883817, P=1.46×10(-6)); 12q13.13 (rs4761974, P=8.71×10(-7)); 20p12.1 (rs6135309, P=3.69×10(-6)); and 4p15.31 (rs7664442, P=2.26×10(-6)). Variants that have been previously related to WML explained only 0.8% to 11.7% more of the variance in WML progression than age, vascular risk factors, and baseline WML burden. CONCLUSIONS: Common genetic factors contribute little to the progression of age-related WML in middle-aged and older adults. Future research on determinants of WML progression should focus more on environmental, lifestyle, or host-related biological factors.
Keywords: Adult; Aged; Cohort Studies; Disease Progression; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Leukoencephalopathies; Male; Middle Aged; Prospective Studies; White Matter

Years of able life in older persons--the role of cardiovascular imaging and biomarkers: the Cardiovascular Health Study. - Alshawabkeh, Laith I; Yee, Laura M; Gardin, Julius M; Gottdiener, John S; Odden, Michelle C; Bartz, Traci M; Arnold, Alice M; Mukamal, Kenneth J; Wallace, Robert B (J Am Heart Assoc, 2015)
BACKGROUND: As the U.S. population grows older, there is greater need to examine physical independence. Previous studies have assessed risk factors in relation to either disability or mortality, but an outcome that combines both is still needed. METHODS AND RESULTS: The Cardiovascular Health Study is a population-based, prospective study where participants underwent baseline echocardiogram, measurement of carotid intima-media thickness (IMT), and various biomarkers, then followed for up to 18 years. Years of able life (YAL) constituted the number of years the participant was able to perform all activities of daily living. Linear regression was used to model the relationship between selected measures and outcomes, adjusted for confounding variables. Among 4902 participants, mean age was 72.6 ± 5.4 years, median YAL for males was 8.8 (interquartile range [IQR], 4.3 to 13.8) and 10.3 (IQR, 5.8 to 15.8) for females. Reductions in YAL in the fully adjusted model for females and males, respectively, were: -1.34 (95% confidence interval [CI], -2.18, -0.49) and -1.41 (95% CI, -2.03, -0.8) for abnormal left ventricular (LV) ejection fraction, -0.5 (95% CI, -0.78, -0.22) and -0.62 (95% CI, -0.87, -0.36) per SD increase in LV mass, -0.5 (95% CI, -0.7, -0.29) and -0.79 (95% CI, -0.99, -0.58) for IMT, -0.5 (95% CI, -0.64, -0.37) and -0.79 (95% CI, -0.94, -0.65) for N-terminal pro-brain natriuretic peptide, -1.08 (95% CI, -1.34, -0.83) and -0.73 (95% CI, -0.97, -0.5) for high-sensitivity troponin-T, and -0.26 (95% CI, -0.42, -0.09) and -0.23 (95% CI, -0.41, -0.05) for procollagen-III N-terminal propeptide. Most tested variables remained significant even after adjusting for incident cardiovascular (CV) disease. CONCLUSIONS: In this population-based cohort, variables obtained by CV imaging and biomarkers of inflammation, coagulation, atherosclerosis, myocardial injury and stress, and cardiac collagen turnover were associated with YAL, an important outcome that integrates physical ability and longevity in older persons.
Keywords: Activities of Daily Living; Aged; Biomarkers; Cardiovascular Diseases; Carotid Intima-Media Thickness; Echocardiography; Female; Humans; Independent Living; Male; Natriuretic Peptide, Brain; Peptide Fragments; Procollagen; Prospective Studies; Stroke Volume; Troponin I

-3 Polyunsaturated Fatty Acid Biomarkers and Coronary Heart Disease: Pooling Project of 19 Cohort Studies - Del Gobbo, L. C.; Imamura, F.; Aslibekyan, S.; Marklund, M.; Virtanen, J. K.; Wennberg, M.; Yakoob, M. Y.; Chiuve, S. E.; Dela Cruz, L.; Frazier-Wood, A. C.; Fretts, A. M.; Guallar, E.; et al. (JAMA Intern Med, 2016)
-3 polyunsaturated fatty acids for primary prevention of coronary heart disease (CHD) remains controversial. Most prior longitudinal studies evaluated self-reported consumption rather than biomarkers.\ -3) for incident CHD.\ A global consortium of 19 studies identified by November 2014.\ -3 biomarkers and ascertained CHD.\ -6 levels, and FADS desaturase genes.\ Incident total CHD, fatal CHD, and nonfatal myocardial infarction (MI).\ -3 biomarkers ALA, DPA, and DHA were associated with a lower risk of fatal CHD, with relative risks (RRs) of 0.91 (95% CI, 0.84-0.98) for ALA, 0.90 (95% CI, 0.85-0.96) for DPA, and 0.90 (95% CI, 0.84-0.96) for DHA. Although DPA was associated with a lower risk of total CHD (RR, 0.94; 95% CI, 0.90-0.99), ALA (RR, 1.00; 95% CI, 0.95-1.05), EPA (RR, 0.94; 95% CI, 0.87-1.02), and DHA (RR, 0.95; 95% CI, 0.91-1.00) were not. Significant associations with nonfatal MI were not evident. Associations appeared generally stronger in phospholipids and total plasma. Restricted cubic splines did not identify evidence of nonlinearity in dose responses.\ -3 fatty acids are associated with a modestly lower incidence of fatal CHD.

52 Genetic Loci Influencing Myocardial Mass. - van der Harst, Pim; van Setten, Jessica; Verweij, Niek; Vogler, Georg; Franke, Lude; Maurano, Matthew T; Wang, Xinchen; Mateo Leach, Irene; Eijgelsheim, Mark; Sotoodehnia, Nona; Hayward, Caroline; Sorice, Rossella; et al. (J Am Coll Cardiol, 2016)
BACKGROUND: Myocardial mass is a key determinant of cardiac muscle function and hypertrophy. Myocardial depolarization leading to cardiac muscle contraction is reflected by the amplitude and duration of the QRS complex on the electrocardiogram (ECG). Abnormal QRS amplitude or duration reflect changes in myocardial mass and conduction, and are associated with increased risk of heart failure and death. OBJECTIVES: This meta-analysis sought to gain insights into the genetic determinants of myocardial mass. METHODS: We carried out a genome-wide association meta-analysis of 4 QRS traits in up to 73,518 individuals of European ancestry, followed by extensive biological and functional assessment. RESULTS: We identified 52 genomic loci, of which 32 are novel, that are reliably associated with 1 or more QRS phenotypes at p < 1 × 10(-8). These loci are enriched in regions of open chromatin, histone modifications, and transcription factor binding, suggesting that they represent regions of the genome that are actively transcribed in the human heart. Pathway analyses provided evidence that these loci play a role in cardiac hypertrophy. We further highlighted 67 candidate genes at the identified loci that are preferentially expressed in cardiac tissue and associated with cardiac abnormalities in Drosophila melanogaster and Mus musculus. We validated the regulatory function of a novel variant in the SCN5A/SCN10A locus in vitro and in vivo. CONCLUSIONS: Taken together, our findings provide new insights into genes and biological pathways controlling myocardial mass and may help identify novel therapeutic targets.

Association of the IGF1 gene with fasting insulin levels. - Willems, Sara M; Cornes, Belinda K; Brody, Jennifer A; Morrison, Alanna C; Lipovich, Leonard; Dauriz, Marco; Chen, Yuning; Liu, Ching-Ti; Rybin, Denis V; Gibbs, Richard A; Muzny, Donna; Pankow, James S; et al. (Eur J Hum Genet, 2016)
Insulin-like growth factor 1 (IGF-I) has been associated with insulin resistance. Genome-wide association studies (GWASs) of fasting insulin (FI) identified single-nucleotide variants (SNVs) near the IGF1 gene, raising two hypotheses: (1) these associations are mediated by IGF-I levels and (2) these noncoding variants either tag other functional variants in the region or are directly functional. In our study, analyses including 5141 individuals from population-based cohorts suggest that FI associations near IGF1 are not mediated by IGF-I. Analyses of targeted sequencing data in 3539 individuals reveal a large number of novel rare variants at the IGF1 locus and show a FI association with a subset of rare nonsynonymous variants (PSKAT=5.7 × 10(-4)). Conditional analyses suggest that this association is partly explained by the GWAS signal and the presence of a residual independent rare variant effect (Pconditional=0.019). Annotation using ENCODE data suggests that the GWAS variants may have a direct functional role in insulin biology. In conclusion, our study provides insight into variation present at the IGF1 locus and into the genetic architecture underlying FI levels, suggesting that FI associations of SNVs near IGF1 are not mediated by IGF-I and suggesting a role for both rare nonsynonymous and common functional variants in insulin biology.

Cardiovascular Disease, Mortality Risk, and Healthcare Costs by Lipoprotein(a) Levels According to Low-density Lipoprotein Cholesterol Levels in Older High-risk Adults. - Zhao, Yanglu; Delaney, Joseph A; Quek, Ruben G W; Gardin, Julius M; Hirsch, Calvin H; Gandra, Shravanthi R; Wong, Nathan D (Clin Cardiol, 2016)
BACKGROUND: The value of lipoprotein(a) (Lp[a]) for predicting cardiovascular disease (CVD) across low-density lipoprotein cholesterol (LDL-C) is uncertain. HYPOTHESIS: In older high-risk adults, higher LDL and Lp(a) combined would be associated with higher CVD risk and more healthcare costs. METHODS: We included 3251 high-risk subjects (prior CVD, diabetes, or 10-year Framingham CVD risk >20%) age ≥65 years from the Cardiovascular Health Study and examined the relation of Lp(a) tertiles with incident CVD, coronary heart disease (CHD), and all-cause mortality within LDL-C strata (spanning <70 mg/dL to ≥160 mg/dL). We also examined 1-year all-cause and CVD healthcare costs from Medicare claims. RESULTS: Over a 22.5-year follow-up, higher Lp(a) levels predicted CVD and total mortality (both standardized hazard ratio [HR]: 1.06, P < 0.01), whereas higher LDL-C levels predicted higher CHD (standardized HR: 1.09, P < 0.01) but lower total mortality (standardized HR: 0.94, P < 0.001). Adjusted HRs in the highest (vs lowest) tertile of Lp(a) level were 1.95 (P = 0.06) for CVD events and 2.68 (P = 0.03) for CHD events when LDL-C was <70 mg/dL. One-year all-cause healthcare costs were increased for Lp(a) ($771 per SD of 56 µg/mL [P = 0.03], $1976 for Lp(a) 25-64 µg/mL vs <25 µg/mL [P = 0.02], and $1648 for Lp(a) ≥65 µg/mL vs <25 µg/mL [P = 0.054]) but not LDL-C. CONCLUSIONS: In older high-risk adults, increased Lp(a) levels were associated with higher CVD risk, especially in those with LDL-C <70 mg/dL, and with higher healthcare costs.

Changes in Depressive Symptoms and Subsequent Risk of Stroke in the Cardiovascular Health Study. - Gilsanz, Paola; Kubzansky, Laura D; Tchetgen Tchetgen, Eric J; Wang, Qianyi; Kawachi, Ichiro; Patton, Kristen K; Fitzpatrick, Annette L; Kop, Willem J; Longstreth, W T; Glymour, M Maria (Stroke, 2016)
BACKGROUND AND PURPOSE: Depression is associated with stroke, but the effects of changes in depressive symptoms on stroke risk are not well understood. This study examined whether depressive symptom changes across 2 successive annual assessments were associated with incident stroke the following year. METHODS: We used visit data from 4319 participants of the Cardiovascular Health Study who were stroke free at baseline to examine whether changes in depressive symptoms classified across 2 consecutive annual assessments predicted incident first stroke during the subsequent year. Depressive symptoms were assessed using the 10-item Center for Epidemiologic Studies Depression scale (high versus low at ≥10). Survival models were inverse probability weighted to adjust for demographics, health behaviors, medical conditions, past depressive symptoms, censoring, and survival. RESULTS: During follow-up, 334 strokes occurred. Relative to stable low scores of depressive symptoms, improved depression symptoms were associated with almost no excess risk of stroke (adjusted hazards ratio, 1.02; 95% confidence interval, 0.66-1.58). New-onset symptoms were nonsignificantly associated with elevated stroke risk (adjusted hazards ratio, 1.44; 95% confidence interval, 0.97-2.14), whereas persistently high depressive symptoms were associated with elevated adjusted hazard of all-cause stroke (adjusted hazards ratio, 1.65; 95% confidence interval, 1.06-2.56). No evidence for effect modification by race, age, or sex was found. CONCLUSIONS: Persistently high symptoms of depression predicted elevated hazard of stroke. Participants with improved depressive symptoms had no elevation in stroke risk. Such findings suggest that strategies to reduce depressive symptoms may ameliorate stroke risk.

Common variants in DRD2 are associated with sleep duration: the CARe consortium. - Cade, Brian E; Gottlieb, Daniel J; Lauderdale, Diane S; Bennett, David A; Buchman, Aron S; Buxbaum, Sarah G; De Jager, Philip L; Evans, Daniel S; Fulop, Tibor; Gharib, Sina A; Johnson, W Craig; Kim, Hyun; et al. (Hum Mol Genet, 2016)
Sleep duration is implicated in the etiologies of chronic diseases and premature mortality. However, the genetic basis for sleep duration is poorly defined. We sought to identify novel genetic components influencing sleep duration in a multi-ethnic sample. Meta-analyses were conducted of genetic associations with self-reported, habitual sleep duration from seven Candidate Gene Association Resource (CARe) cohorts of over 25 000 individuals of African, Asian, European and Hispanic American ancestry. All individuals were genotyped for ∼50 000 SNPs from 2000 candidate heart, lung, blood and sleep genes. African-Americans had additional genome-wide genotypes. Four cohorts provided replication. A SNP (rs17601612) in the dopamine D2 receptor gene (DRD2) was significantly associated with sleep duration (P = 9.8 × 10(-7)). Conditional analysis identified a second DRD2 signal with opposite effects on sleep duration. In exploratory analysis, suggestive association was observed for rs17601612 with polysomnographically determined sleep latency (P = 0.002). The lead DRD2 signal was recently identified in a schizophrenia GWAS, and a genetic risk score of 11 additional schizophrenia GWAS loci genotyped on the IBC array was also associated with longer sleep duration (P = 0.03). These findings support a role for DRD2 in influencing sleep duration. Our work motivates future pharmocogenetics research on alerting agents such as caffeine and modafinil that interact with the dopaminergic pathway and further investigation of genetic overlap between sleep and neuro-psychiatric traits.
Keywords: Cohort Studies; Ethnic Groups; Humans; Polymorphism, Single Nucleotide; Polysomnography; Receptors, Dopamine D2; Sleep; Time Factors

Diagnostic Yield and Clinical Utility of Sequencing Familial Hypercholesterolemia Genes in Patients With Severe Hypercholesterolemia. - Khera, Amit V; Won, Hong-Hee; Peloso, Gina M; Lawson, Kim S; Bartz, Traci M; Deng, Xuan; van Leeuwen, Elisabeth M; Natarajan, Pradeep; Emdin, Connor A; Bick, Alexander G; Morrison, Alanna C; Brody, Jennifer A; et al. (J Am Coll Cardiol, 2016)
BACKGROUND: Approximately 7% of American adults have severe hypercholesterolemia (untreated low-density lipoprotein [LDL] cholesterol ≥190 mg/dl), which may be due to familial hypercholesterolemia (FH). Lifelong LDL cholesterol elevations in FH mutation carriers may confer coronary artery disease (CAD) risk beyond that captured by a single LDL cholesterol measurement. OBJECTIVES: This study assessed the prevalence of an FH mutation among those with severe hypercholesterolemia and determined whether CAD risk varies according to mutation status beyond the observed LDL cholesterol level. METHODS: Three genes causative for FH (LDLR, APOB, and PCSK9) were sequenced in 26,025 participants from 7 case-control studies (5,540 CAD case subjects, 8,577 CAD-free control subjects) and 5 prospective cohort studies (11,908 participants). FH mutations included loss-of-function variants in LDLR, missense mutations in LDLR predicted to be damaging, and variants linked to FH in ClinVar, a clinical genetics database. RESULTS: Among 20,485 CAD-free control and prospective cohort participants, 1,386 (6.7%) had LDL cholesterol ≥190 mg/dl; of these, only 24 (1.7%) carried an FH mutation. Within any stratum of observed LDL cholesterol, risk of CAD was higher among FH mutation carriers than noncarriers. Compared with a reference group with LDL cholesterol <130 mg/dl and no mutation, participants with LDL cholesterol ≥190 mg/dl and no FH mutation had a 6-fold higher risk for CAD (odds ratio: 6.0; 95% confidence interval: 5.2 to 6.9), whereas those with both LDL cholesterol ≥190 mg/dl and an FH mutation demonstrated a 22-fold increased risk (odds ratio: 22.3; 95% confidence interval: 10.7 to 53.2). In an analysis of participants with serial lipid measurements over many years, FH mutation carriers had higher cumulative exposure to LDL cholesterol than noncarriers. CONCLUSIONS: Among participants with LDL cholesterol ≥190 mg/dl, gene sequencing identified an FH mutation in <2%. However, for any observed LDL cholesterol, FH mutation carriers had substantially increased risk for CAD.

Discovery of Genetic Variation on Chromosome 5q22 Associated with Mortality in Heart Failure. - Smith, J Gustav; Felix, Janine F; Morrison, Alanna C; Kalogeropoulos, Andreas; Trompet, Stella; Wilk, Jemma B; Gidlöf, Olof; Wang, Xinchen; Morley, Michael; Mendelson, Michael; Joehanes, Roby; Ligthart, Symen; et al. (PLoS Genet, 2016)
Failure of the human heart to maintain sufficient output of blood for the demands of the body, heart failure, is a common condition with high mortality even with modern therapeutic alternatives. To identify molecular determinants of mortality in patients with new-onset heart failure, we performed a meta-analysis of genome-wide association studies and follow-up genotyping in independent populations. We identified and replicated an association for a genetic variant on chromosome 5q22 with 36% increased risk of death in subjects with heart failure (rs9885413, P = 2.7x10-9). We provide evidence from reporter gene assays, computational predictions and epigenomic marks that this polymorphism increases activity of an enhancer region active in multiple human tissues. The polymorphism was further reproducibly associated with a DNA methylation signature in whole blood (P = 4.5x10-40) that also associated with allergic sensitization and expression in blood of the cytokine TSLP (P = 1.1x10-4). Knockdown of the transcription factor predicted to bind the enhancer region (NHLH1) in a human cell line (HEK293) expressing NHLH1 resulted in lower TSLP expression. In addition, we observed evidence of recent positive selection acting on the risk allele in populations of African descent. Our findings provide novel genetic leads to factors that influence mortality in patients with heart failure.

A DNA methylation biomarker of alcohol consumption. - Liu, C; Marioni, R E; Hedman, Å K; Pfeiffer, L; Tsai, P-C; Reynolds, L M; Just, A C; Duan, Q; Boer, C G; Tanaka, T; Elks, C E; Aslibekyan, S; et al. (Mol Psychiatry, 2016)
The lack of reliable measures of alcohol intake is a major obstacle to the diagnosis and treatment of alcohol-related diseases. Epigenetic modifications such as DNA methylation may provide novel biomarkers of alcohol use. To examine this possibility, we performed an epigenome-wide association study of methylation of cytosine-phosphate-guanine dinucleotide (CpG) sites in relation to alcohol intake in 13 population-based cohorts (ntotal=13 317; 54% women; mean age across cohorts 42-76 years) using whole blood (9643 European and 2423 African ancestries) or monocyte-derived DNA (588 European, 263 African and 400 Hispanic ancestry) samples. We performed meta-analysis and variable selection in whole-blood samples of people of European ancestry (n=6926) and identified 144 CpGs that provided substantial discrimination (area under the curve=0.90-0.99) for current heavy alcohol intake (⩾42 g per day in men and ⩾28 g per day in women) in four replication cohorts. The ancestry-stratified meta-analysis in whole blood identified 328 (9643 European ancestry samples) and 165 (2423 African ancestry samples) alcohol-related CpGs at Bonferroni-adjusted P<1 × 10(-7). Analysis of the monocyte-derived DNA (n=1251) identified 62 alcohol-related CpGs at P<1 × 10(-7). In whole-blood samples of people of European ancestry, we detected differential methylation in two neurotransmitter receptor genes, the γ-Aminobutyric acid-A receptor delta and γ-aminobutyric acid B receptor subunit 1; their differential methylation was associated with expression levels of a number of genes involved in immune function. In conclusion, we have identified a robust alcohol-related DNA methylation signature and shown the potential utility of DNA methylation as a clinically useful diagnostic test to detect current heavy alcohol consumption.Molecular Psychiatry advance online publication, 15 November 2016; doi:10.1038/mp.2016.192.

DNA methylation signatures of chronic low-grade inflammation are associated with complex diseases. - Ligthart, Symen; Marzi, Carola; Aslibekyan, Stella; Mendelson, Michael M; Conneely, Karen N; Tanaka, Toshiko; Colicino, Elena; Waite, Lindsay L; Joehanes, Roby; Guan, Weihua; Brody, Jennifer A; Elks, Cathy; et al. (Genome Biol, 2016)
BACKGROUND: Chronic low-grade inflammation reflects a subclinical immune response implicated in the pathogenesis of complex diseases. Identifying genetic loci where DNA methylation is associated with chronic low-grade inflammation may reveal novel pathways or therapeutic targets for inflammation. RESULTS: We performed a meta-analysis of epigenome-wide association studies (EWAS) of serum C-reactive protein (CRP), which is a sensitive marker of low-grade inflammation, in a large European population (n = 8863) and trans-ethnic replication in African Americans (n = 4111). We found differential methylation at 218 CpG sites to be associated with CRP (P < 1.15 × 10(-7)) in the discovery panel of European ancestry and replicated (P < 2.29 × 10(-4)) 58 CpG sites (45 unique loci) among African Americans. To further characterize the molecular and clinical relevance of the findings, we examined the association with gene expression, genetic sequence variants, and clinical outcomes. DNA methylation at nine (16%) CpG sites was associated with whole blood gene expression in cis (P < 8.47 × 10(-5)), ten (17%) CpG sites were associated with a nearby genetic variant (P < 2.50 × 10(-3)), and 51 (88%) were also associated with at least one related cardiometabolic entity (P < 9.58 × 10(-5)). An additive weighted score of replicated CpG sites accounted for up to 6% inter-individual variation (R2) of age-adjusted and sex-adjusted CRP, independent of known CRP-related genetic variants. CONCLUSION: We have completed an EWAS of chronic low-grade inflammation and identified many novel genetic loci underlying inflammation that may serve as targets for the development of novel therapeutic interventions for inflammation.

Echocardiographic Predictors of Sudden Cardiac Death: The Atherosclerosis Risk in Communities Study and Cardiovascular Health Study. - Konety, Suma H; Koene, Ryan J; Norby, Faye L; Wilsdon, Tony; Alonso, Alvaro; Siscovick, David; Sotoodehnia, Nona; Gottdiener, John; Fox, Ervin R; Chen, Lin Y; Adabag, Selcuk; Folsom, Aaron R (Circ Cardiovasc Imaging, 2016)
BACKGROUND: This study assessed the echocardiographic predictors of sudden cardiac death (SCD) within 2 population-based cohorts. METHODS AND RESULTS: Echocardiograms were obtained on 2383 participants (1993-1995) from the ARIC study (Atherosclerosis Risk in Communities; 100% black) and 5366 participants (1987-1989 and 1994-1995) from the CHS (Cardiovascular Health Study). The main outcome was physician-adjudicated SCD. We used Cox proportional-hazards models with incident coronary heart disease and heart failure as time-dependent covariates to assess the association between echocardiographic variables and SCD, adjusting for Framingham risk score variables, coronary heart disease, and renal function. Cohort-specific results were meta-analyzed. During a median follow-up of 7.3 and 13.1 years, 44 ARIC study participants and 275 CHS participants had SCD, respectively. In the meta-analyzed results, the adjusted hazard ratios (95% confidence intervals) for predictors of SCD were 3.07 (2.29-4.11) for reduced left ventricular ejection fraction; 1.85 (1.36-2.52) for mitral annular calcification; 1.64 (1.07-2.51) for mitral E/A >1.5, and 1.52 (1.14-2.02) for mitral E/A <0.7 (versus mitral E/A 0.7-1.5); 1.30 (1.15-1.48) per 1 SD increase in left ventricular mass; and 1.15 (1.02-1.30) per 1 SD increase in left atrial diameter. A receiver-operating characteristic model for prediction of SCD using Framingham risk score variables had a C statistic of 0.61 for ARIC study and 0.67 for CHS; the full multivariable model including all echocardiographic variables had a C statistic of 0.76 for ARIC study and 0.74 for CHS. CONCLUSIONS: In addition to reduced left ventricular ejection fraction, we identified other echocardiographic-derived variables predictive for SCD that provided incremental value compared with clinical risk factors.

An Empirical Comparison of Joint and Stratified Frameworks for Studying G × E Interactions: Systolic Blood Pressure and Smoking in the CHARGE Gene-Lifestyle Interactions Working Group. - Sung, Yun Ju; Winkler, Thomas W; Manning, Alisa K; Aschard, Hugues; Gudnason, Vilmundur; Harris, Tamara B; Smith, Albert V; Boerwinkle, Eric; Brown, Michael R; Morrison, Alanna C; Fornage, Myriam; Lin, Li-An; et al. (Genet Epidemiol, 2016)
Studying gene-environment (G × E) interactions is important, as they extend our knowledge of the genetic architecture of complex traits and may help to identify novel variants not detected via analysis of main effects alone. The main statistical framework for studying G × E interactions uses a single regression model that includes both the genetic main and G × E interaction effects (the "joint" framework). The alternative "stratified" framework combines results from genetic main-effect analyses carried out separately within the exposed and unexposed groups. Although there have been several investigations using theory and simulation, an empirical comparison of the two frameworks is lacking. Here, we compare the two frameworks using results from genome-wide association studies of systolic blood pressure for 3.2 million low frequency and 6.5 million common variants across 20 cohorts of European ancestry, comprising 79,731 individuals. Our cohorts have sample sizes ranging from 456 to 22,983 and include both family-based and population-based samples. In cohort-specific analyses, the two frameworks provided similar inference for population-based cohorts. The agreement was reduced for family-based cohorts. In meta-analyses, agreement between the two frameworks was less than that observed in cohort-specific analyses, despite the increased sample size. In meta-analyses, agreement depended on (1) the minor allele frequency, (2) inclusion of family-based cohorts in meta-analysis, and (3) filtering scheme. The stratified framework appears to approximate the joint framework well only for common variants in population-based cohorts. We conclude that the joint framework is the preferred approach and should be used to control false positives when dealing with low-frequency variants and/or family-based cohorts.

Epigenetic Signatures of Cigarette Smoking. - Joehanes, Roby; Just, Allan C; Marioni, Riccardo E; Pilling, Luke C; Reynolds, Lindsay M; Mandaviya, Pooja R; Guan, Weihua; Xu, Tao; Elks, Cathy E; Aslibekyan, Stella; Moreno-Macias, Hortensia; Smith, Jennifer A; et al. (Circ Cardiovasc Genet, 2016)
BACKGROUND: DNA methylation leaves a long-term signature of smoking exposure and is one potential mechanism by which tobacco exposure predisposes to adverse health outcomes, such as cancers, osteoporosis, lung, and cardiovascular disorders. METHODS AND RESULTS: To comprehensively determine the association between cigarette smoking and DNA methylation, we conducted a meta-analysis of genome-wide DNA methylation assessed using the Illumina BeadChip 450K array on 15 907 blood-derived DNA samples from participants in 16 cohorts (including 2433 current, 6518 former, and 6956 never smokers). Comparing current versus never smokers, 2623 cytosine-phosphate-guanine sites (CpGs), annotated to 1405 genes, were statistically significantly differentially methylated at Bonferroni threshold of P<1×10(-7) (18 760 CpGs at false discovery rate <0.05). Genes annotated to these CpGs were enriched for associations with several smoking-related traits in genome-wide studies including pulmonary function, cancers, inflammatory diseases, and heart disease. Comparing former versus never smokers, 185 of the CpGs that differed between current and never smokers were significant P<1×10(-7) (2623 CpGs at false discovery rate <0.05), indicating a pattern of persistent altered methylation, with attenuation, after smoking cessation. Transcriptomic integration identified effects on gene expression at many differentially methylated CpGs. CONCLUSIONS: Cigarette smoking has a broad impact on genome-wide methylation that, at many loci, persists many years after smoking cessation. Many of the differentially methylated genes were novel genes with respect to biological effects of smoking and might represent therapeutic targets for prevention or treatment of tobacco-related diseases. Methylation at these sites could also serve as sensitive and stable biomarkers of lifetime exposure to tobacco smoke.

Exome Genotyping Identifies Pleiotropic Variants Associated with Red Blood Cell Traits. - Chami, Nathalie; Chen, Ming-Huei; Slater, Andrew J; Eicher, John D; Evangelou, Evangelos; Tajuddin, Salman M; Love-Gregory, Latisha; Kacprowski, Tim; Schick, Ursula M; Nomura, Akihiro; Giri, Ayush; Lessard, Samuel; et al. (Am J Hum Genet, 2016)
Red blood cell (RBC) traits are important heritable clinical biomarkers and modifiers of disease severity. To identify coding genetic variants associated with these traits, we conducted meta-analyses of seven RBC phenotypes in 130,273 multi-ethnic individuals from studies genotyped on an exome array. After conditional analyses and replication in 27,480 independent individuals, we identified 16 new RBC variants. We found low-frequency missense variants in MAP1A (rs55707100, minor allele frequency [MAF] = 3.3%, p = 2 × 10(-10) for hemoglobin [HGB]) and HNF4A (rs1800961, MAF = 2.4%, p < 3 × 10(-8) for hematocrit [HCT] and HGB). In African Americans, we identified a nonsense variant in CD36 associated with higher RBC distribution width (rs3211938, MAF = 8.7%, p = 7 × 10(-11)) and showed that it is associated with lower CD36 expression and strong allelic imbalance in ex vivo differentiated human erythroblasts. We also identified a rare missense variant in ALAS2 (rs201062903, MAF = 0.2%) associated with lower mean corpuscular volume and mean corpuscular hemoglobin (p < 8 × 10(-9)). Mendelian mutations in ALAS2 are a cause of sideroblastic anemia and erythropoietic protoporphyria. Gene-based testing highlighted three rare missense variants in PKLR, a gene mutated in Mendelian non-spherocytic hemolytic anemia, associated with HGB and HCT (SKAT p < 8 × 10(-7)). These rare, low-frequency, and common RBC variants showed pleiotropy, being also associated with platelet, white blood cell, and lipid traits. Our association results and functional annotation suggest the involvement of new genes in human erythropoiesis. We also confirm that rare and low-frequency variants play a role in the architecture of complex human traits, although their phenotypic effect is generally smaller than originally anticipated.

Fine-mapping, novel loci identification, and SNP association transferability in a genome-wide association study of QRS duration in African Americans. - Evans, Daniel S; Avery, Christy L; Nalls, Mike A; Li, Guo; Barnard, John; Smith, Erin N; Tanaka, Toshiko; Butler, Anne M; Buxbaum, Sarah G; Alonso, Alvaro; Arking, Dan E; Berenson, Gerald S; et al. (Hum Mol Genet, 2016)
The electrocardiographic QRS duration, a measure of ventricular depolarization and conduction, is associated with cardiovascular mortality. While single nucleotide polymorphisms (SNPs) associated with QRS duration have been identified at 22 loci in populations of European descent, the genetic architecture of QRS duration in non-European populations is largely unknown. We therefore performed a genome-wide association study (GWAS) meta-analysis of QRS duration in 13,031 African Americans from ten cohorts and a transethnic GWAS meta-analysis with additional results from populations of European descent. In the African American GWAS, a single genome-wide significant SNP association was identified (rs3922844, P = 4 × 10(-14)) in intron 16 of SCN5A, a voltage-gated cardiac sodium channel gene. The QRS-prolonging rs3922844 C allele was also associated with decreased SCN5A RNA expression in human atrial tissue (P = 1.1 × 10(-4)). High density genotyping revealed that the SCN5A association region in African Americans was confined to intron 16. Transethnic GWAS meta-analysis identified novel SNP associations on chromosome 18 in MYL12A (rs1662342, P = 4.9 × 10(-8)) and chromosome 1 near CD1E and SPTA1 (rs7547997, P = 7.9 × 10(-9)). The 22 QRS loci previously identified in populations of European descent were enriched for significant SNP associations with QRS duration in African Americans (P = 9.9 × 10(-7)), and index SNP associations in or near SCN5A, SCN10A, CDKN1A, NFIA, HAND1, TBX5 and SETBP1 replicated in African Americans. In summary, rs3922844 was associated with QRS duration and SCN5A expression, two novel QRS loci were identified using transethnic meta-analysis, and a significant proportion of QRS-SNP associations discovered in populations of European descent were transferable to African Americans when adequate power was achieved.

{Gene-gene Interaction Analyses for Atrial Fibrillation - Lin, H.; Mueller-Nurasyid, M.; Smith, A. V.; Arking, D. E.; Barnard, J.; Bartz, T. M.; Lunetta, K. L.; Lohman, K.; Kleber, M. E.; Lubitz, S. A.; Geelhoed, B.; Trompet, S.; et al. (Sci Rep, 2016)
{Atrial fibrillation (AF) is a heritable disease that affects more than thirty million individuals worldwide. Extensive efforts have been devoted to the study of genetic determinants of AF. The objective of our study is to examine the effect of gene-gene interaction on AF susceptibility. We performed a large-scale association analysis of gene-gene interactions with AF in 8,173 AF cases, and 65,237 AF-free referents collected from 15 studies for discovery. We examined putative interactions between genome-wide SNPs and 17 known AF-related SNPs. The top interactions were then tested for association in an independent cohort for replication, which included more than 2,363 AF cases and 114,746 AF-free referents. One interaction, between rs7164883 at the HCN4 locus and rs4980345 at the SLC28A1 locus, was found to be significantly associated with AF in the discovery cohorts (interaction OR = 1.44, 95% CI: 1.27-1.65

General Framework for Meta-Analysis of Haplotype Association Tests. - Wang, Shuai; Zhao, Jing Hua; An, Ping; Guo, Xiuqing; Jensen, Richard A; Marten, Jonathan; Huffman, Jennifer E; Meidtner, Karina; Boeing, Heiner; Campbell, Archie; Rice, Kenneth M; Scott, Robert A; et al. (Genet Epidemiol, 2016)
For complex traits, most associated single nucleotide variants (SNV) discovered to date have a small effect, and detection of association is only possible with large sample sizes. Because of patient confidentiality concerns, it is often not possible to pool genetic data from multiple cohorts, and meta-analysis has emerged as the method of choice to combine results from multiple studies. Many meta-analysis methods are available for single SNV analyses. As new approaches allow the capture of low frequency and rare genetic variation, it is of interest to jointly consider multiple variants to improve power. However, for the analysis of haplotypes formed by multiple SNVs, meta-analysis remains a challenge, because different haplotypes may be observed across studies. We propose a two-stage meta-analysis approach to combine haplotype analysis results. In the first stage, each cohort estimate haplotype effect sizes in a regression framework, accounting for relatedness among observations if appropriate. For the second stage, we use a multivariate generalized least square meta-analysis approach to combine haplotype effect estimates from multiple cohorts. Haplotype-specific association tests and a global test of independence between haplotypes and traits are obtained within our framework. We demonstrate through simulation studies that we control the type-I error rate, and our approach is more powerful than inverse variance weighted meta-analysis of single SNV analysis when haplotype effects are present. We replicate a published haplotype association between fasting glucose-associated locus (G6PC2) and fasting glucose in seven studies from the Cohorts for Heart and Aging Research in Genomic Epidemiology Consortium and we provide more precise haplotype effect estimates.

{Genetic associations at 53 loci highlight cell types and biological pathways relevant for kidney function - Pattaro, C.; Teumer, A.; Gorski, M.; Chu, A. Y.; Li, M.; Mijatovic, V.; Garnaas, M.; Tin, A.; Sorice, R.; Li, Y.; Taliun, D.; Olden, M.; et al. (Nat Commun, 2016)
Reduced glomerular filtration rate defines chronic kidney disease and is associated with cardiovascular and all-cause mortality. We conducted a meta-analysis of genome-wide association studies for estimated glomerular filtration rate (eGFR), combining data across 133,413 individuals with replication in up to 42,166 individuals. We identify 24 new and confirm 29 previously identified loci. Of these 53 loci, 19 associate with eGFR among individuals with diabetes. Using bioinformatics, we show that identified genes at eGFR loci are enriched for expression in kidney tissues and in pathways relevant for kidney development and transmembrane transporter activity, kidney structure, and regulation of glucose metabolism. Chromatin state mapping and DNase I hypersensitivity analyses across adult tissues demonstrate preferential mapping of associated variants to regulatory regions in kidney but not extra-renal tissues. These findings suggest that genetic determinants of eGFR are mediated largely through direct effects within the kidney and highlight important cell types and biological pathways.

Genetic Variants Associated with Circulating Parathyroid Hormone. - Robinson-Cohen, Cassianne; Lutsey, Pamela L; Kleber, Marcus E; Nielson, Carrie M; Mitchell, Braxton D; Bis, Joshua C; Eny, Karen M; Portas, Laura; Eriksson, Joel; Lorentzon, Mattias; Koller, Daniel L; Milaneschi, Yuri; et al. (J Am Soc Nephrol, 2016)
Parathyroid hormone (PTH) is a primary calcium regulatory hormone. Elevated serum PTH concentrations in primary and secondary hyperparathyroidism have been associated with bone disease, hypertension, and in some studies, cardiovascular mortality. Genetic causes of variation in circulating PTH concentrations are incompletely understood. We performed a genome-wide association study of serum PTH concentrations among 29,155 participants of European ancestry from 13 cohort studies (n=22,653 and n=6502 in discovery and replication analyses, respectively). We evaluated the association of single nucleotide polymorphisms (SNPs) with natural log-transformed PTH concentration adjusted for age, sex, season, study site, and principal components of ancestry. We discovered associations of SNPs from five independent regions with serum PTH concentration, including the strongest association with rs6127099 upstream of CYP24A1 (P=4.2 × 10(-53)), a gene that encodes the primary catabolic enzyme for 1,25-dihydroxyvitamin D and 25-dihydroxyvitamin D. Each additional copy of the minor allele at this SNP associated with 7% higher serum PTH concentration. The other SNPs associated with serum PTH concentration included rs4074995 within RGS14 (P=6.6 × 10(-17)), rs219779 adjacent to CLDN14 (P=3.5 × 10(-16)), rs4443100 near RTDR1 (P=8.7 × 10(-9)), and rs73186030 near CASR (P=4.8 × 10(-8)). Of these five SNPs, rs6127099, rs4074995, and rs219779 replicated. Thus, common genetic variants located near genes involved in vitamin D metabolism and calcium and renal phosphate transport associated with differences in circulating PTH concentrations. Future studies could identify the causal variants at these loci, and the clinical and functional relevance of these variants should be pursued.

Genetic variants in RBFOX3 are associated with sleep latency. - Amin, Najaf; Allebrandt, Karla V; van der Spek, Ashley; Müller-Myhsok, Bertram; Hek, Karin; Teder-Laving, Maris; Hayward, Caroline; Esko, Tõnu; van Mill, Josine G; Mbarek, Hamdi; Watson, Nathaniel F; Melville, Scott A; et al. (Eur J Hum Genet, 2016)
Time to fall asleep (sleep latency) is a major determinant of sleep quality. Chronic, long sleep latency is a major characteristic of sleep-onset insomnia and/or delayed sleep phase syndrome. In this study we aimed to discover common polymorphisms that contribute to the genetics of sleep latency. We performed a meta-analysis of genome-wide association studies (GWAS) including 2 572 737 single nucleotide polymorphisms (SNPs) established in seven European cohorts including 4242 individuals. We found a cluster of three highly correlated variants (rs9900428, rs9907432 and rs7211029) in the RNA-binding protein fox-1 homolog 3 gene (RBFOX3) associated with sleep latency (P-values=5.77 × 10(-08), 6.59 × 10(-)(08) and 9.17 × 10(-)(08)). These SNPs were replicated in up to 12 independent populations including 30 377 individuals (P-values=1.5 × 10(-)(02), 7.0 × 10(-)(03) and 2.5 × 10(-)(03); combined meta-analysis P-values=5.5 × 10(-07), 5.4 × 10(-07) and 1.0 × 10(-07)). A functional prediction of RBFOX3 based on co-expression with other genes shows that this gene is predominantly expressed in brain (P-value=1.4 × 10(-316)) and the central nervous system (P-value=7.5 × 10(-)(321)). The predicted function of RBFOX3 based on co-expression analysis with other genes shows that this gene is significantly involved in the release cycle of neurotransmitters including gamma-aminobutyric acid and various monoamines (P-values<2.9 × 10(-11)) that are crucial in triggering the onset of sleep. To conclude, in this first large-scale GWAS of sleep latency we report a novel association of variants in RBFOX3 gene. Further, a functional prediction of RBFOX3 supports the involvement of RBFOX3 with sleep latency.

{The genetics of blood pressure regulation and its target organs from association studies in 342,415 individuals - Ehret, G. B.; Ferreira, T.; Chasman, D. I.; Jackson, A. U.; Schmidt, E. M.; Johnson, T.; Thorleifsson, G.; Luan, J.; Donnelly, L. A.; Kanoni, S.; Petersen, A. K.; Pihur, V.; et al. (Nat Genet, 2016)
To dissect the genetic architecture of blood pressure and assess effects on target organ damage, we analyzed 128,272 SNPs from targeted and genome-wide arrays in 201,529 individuals of European ancestry, and genotypes from an additional 140,886 individuals were used for validation. We identified 66 blood pressure-associated loci, of which 17 were new; 15 harbored multiple distinct association signals. The 66 index SNPs were enriched for cis-regulatory elements, particularly in vascular endothelial cells, consistent with a primary role in blood pressure control through modulation of vascular tone across multiple tissues. The 66 index SNPs combined in a risk score showed comparable effects in 64,421 individuals of non-European descent. The 66-SNP blood pressure risk score was significantly associated with target organ damage in multiple tissues but with minor effects in the kidney. Our findings expand current knowledge of blood pressure-related pathways and highlight tissues beyond the classical renal system in blood pressure regulation.

Genome-Wide Association Analysis of Young-Onset Stroke Identifies a Locus on Chromosome 10q25 Near HABP2. - Cheng, Yu-Ching; Stanne, Tara M; Giese, Anne-Katrin; Ho, Weang Kee; Traylor, Matthew; Amouyel, Philippe; Holliday, Elizabeth G; Malik, Rainer; Xu, Huichun; Kittner, Steven J; Cole, John W; O'Connell, Jeffrey R; et al. (Stroke, 2016)
BACKGROUND AND PURPOSE: Although a genetic contribution to ischemic stroke is well recognized, only a handful of stroke loci have been identified by large-scale genetic association studies to date. Hypothesizing that genetic effects might be stronger for early- versus late-onset stroke, we conducted a 2-stage meta-analysis of genome-wide association studies, focusing on stroke cases with an age of onset <60 years. METHODS: The discovery stage of our genome-wide association studies included 4505 cases and 21 968 controls of European, South-Asian, and African ancestry, drawn from 6 studies. In Stage 2, we selected the lead genetic variants at loci with association P<5×10(-6) and performed in silico association analyses in an independent sample of ≤1003 cases and 7745 controls. RESULTS: One stroke susceptibility locus at 10q25 reached genome-wide significance in the combined analysis of all samples from the discovery and follow-up stages (rs11196288; odds ratio =1.41; P=9.5×10(-9)). The associated locus is in an intergenic region between TCF7L2 and HABP2. In a further analysis in an independent sample, we found that 2 single nucleotide polymorphisms in high linkage disequilibrium with rs11196288 were significantly associated with total plasma factor VII-activating protease levels, a product of HABP2. CONCLUSIONS: HABP2, which encodes an extracellular serine protease involved in coagulation, fibrinolysis, and inflammatory pathways, may be a genetic susceptibility locus for early-onset stroke.
Keywords: Adult; African Continental Ancestry Group; Age of Onset; Aged; Asian Continental Ancestry Group; Brain Ischemia; Chromosomes, Human, Pair 10; Computer Simulation; DNA, Intergenic; European Continental Ancestry Group; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Male; Middle Aged; Odds Ratio; Polymorphism, Single Nucleotide; Serine Endopeptidases; Stroke

Genome-Wide Association Study for Incident Myocardial Infarction and Coronary Heart Disease in Prospective Cohort Studies: The CHARGE Consortium. - Dehghan, Abbas; Bis, Joshua C; White, Charles C; Smith, Albert Vernon; Morrison, Alanna C; Cupples, L Adrienne; Trompet, Stella; Chasman, Daniel I; Lumley, Thomas; Völker, Uwe; Buckley, Brendan M; Ding, Jingzhong; et al. (PLoS One, 2016)
BACKGROUND: Data are limited on genome-wide association studies (GWAS) for incident coronary heart disease (CHD). Moreover, it is not known whether genetic variants identified to date also associate with risk of CHD in a prospective setting. METHODS: We performed a two-stage GWAS analysis of incident myocardial infarction (MI) and CHD in a total of 64,297 individuals (including 3898 MI cases, 5465 CHD cases). SNPs that passed an arbitrary threshold of 5×10-6 in Stage I were taken to Stage II for further discovery. Furthermore, in an analysis of prognosis, we studied whether known SNPs from former GWAS were associated with total mortality in individuals who experienced MI during follow-up. RESULTS: In Stage I 15 loci passed the threshold of 5×10-6; 8 loci for MI and 8 loci for CHD, for which one locus overlapped and none were reported in previous GWAS meta-analyses. We took 60 SNPs representing these 15 loci to Stage II of discovery. Four SNPs near QKI showed nominally significant association with MI (p-value<8.8×10-3) and three exceeded the genome-wide significance threshold when Stage I and Stage II results were combined (top SNP rs6941513: p = 6.2×10-9). Despite excellent power, the 9p21 locus SNP (rs1333049) was only modestly associated with MI (HR = 1.09, p-value = 0.02) and marginally with CHD (HR = 1.06, p-value = 0.08). Among an inception cohort of those who experienced MI during follow-up, the risk allele of rs1333049 was associated with a decreased risk of subsequent mortality (HR = 0.90, p-value = 3.2×10-3). CONCLUSIONS: QKI represents a novel locus that may serve as a predictor of incident CHD in prospective studies. The association of the 9p21 locus both with increased risk of first myocardial infarction and longer survival after MI highlights the importance of study design in investigating genetic determinants of complex disorders.
Keywords: Aged; Cohort Studies; Cooperative Behavior; Coronary Artery Disease; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Male; Middle Aged; Myocardial Infarction; Polymorphism, Single Nucleotide; Prospective Studies

Genome-Wide Association Study of the Modified Stumvoll Insulin Sensitivity Index Identifies BCL2 and FAM19A2 as Novel Insulin Sensitivity Loci. - Walford, Geoffrey A; Gustafsson, Stefan; Rybin, Denis; Stančáková, Alena; Chen, Han; Liu, Ching-Ti; Hong, Jaeyoung; Jensen, Richard A; Rice, Ken; Morris, Andrew P; Mägi, Reedik; Tönjes, Anke; et al. (Diabetes, 2016)
Genome-wide association studies (GWAS) have found few common variants that influence fasting measures of insulin sensitivity. We hypothesized that a GWAS of an integrated assessment of fasting and dynamic measures of insulin sensitivity would detect novel common variants. We performed a GWAS of the modified Stumvoll Insulin Sensitivity Index (ISI) within the Meta-Analyses of Glucose and Insulin-Related Traits Consortium. Discovery for genetic association was performed in 16,753 individuals, and replication was attempted for the 23 most significant novel loci in 13,354 independent individuals. Association with ISI was tested in models adjusted for age, sex, and BMI and in a model analyzing the combined influence of the genotype effect adjusted for BMI and the interaction effect between the genotype and BMI on ISI (model 3). In model 3, three variants reached genome-wide significance: rs13422522 (NYAP2; P = 8.87 × 10(-11)), rs12454712 (BCL2; P = 2.7 × 10(-8)), and rs10506418 (FAM19A2; P = 1.9 × 10(-8)). The association at NYAP2 was eliminated by conditioning on the known IRS1 insulin sensitivity locus; the BCL2 and FAM19A2 associations were independent of known cardiometabolic loci. In conclusion, we identified two novel loci and replicated known variants associated with insulin sensitivity. Further studies are needed to clarify the causal variant and function at the BCL2 and FAM19A2 loci.

Genomewide meta-analysis identifies loci associated with IGF-I and IGFBP-3 levels with impact on age-related traits. - Teumer, Alexander; Qi, Qibin; Nethander, Maria; Aschard, Hugues; Bandinelli, Stefania; Beekman, Marian; Berndt, Sonja I; Bidlingmaier, Martin; Broer, Linda; Cappola, Anne; Ceda, Gian Paolo; Chanock, Stephen; et al. (Aging Cell, 2016)
The growth hormone/insulin-like growth factor (IGF) axis can be manipulated in animal models to promote longevity, and IGF-related proteins including IGF-I and IGF-binding protein-3 (IGFBP-3) have also been implicated in risk of human diseases including cardiovascular diseases, diabetes, and cancer. Through genomewide association study of up to 30 884 adults of European ancestry from 21 studies, we confirmed and extended the list of previously identified loci associated with circulating IGF-I and IGFBP-3 concentrations (IGF1, IGFBP3, GCKR, TNS3, GHSR, FOXO3, ASXL2, NUBP2/IGFALS, SORCS2, and CELSR2). Significant sex interactions, which were characterized by different genotype-phenotype associations between men and women, were found only for associations of IGFBP-3 concentrations with SNPs at the loci IGFBP3 and SORCS2. Analyses of SNPs, gene expression, and protein levels suggested that interplay between IGFBP3 and genes within the NUBP2 locus (IGFALS and HAGH) may affect circulating IGF-I and IGFBP-3 concentrations. The IGF-I-decreasing allele of SNP rs934073, which is an eQTL of ASXL2, was associated with lower adiposity and higher likelihood of survival beyond 90 years. The known longevity-associated variant rs2153960 (FOXO3) was observed to be a genomewide significant SNP for IGF-I concentrations. Bioinformatics analysis suggested enrichment of putative regulatory elements among these IGF-I- and IGFBP-3-associated loci, particularly of rs646776 at CELSR2. In conclusion, this study identified several loci associated with circulating IGF-I and IGFBP-3 concentrations and provides clues to the potential role of the IGF axis in mediating effects of known (FOXO3) and novel (ASXL2) longevity-associated loci.

Global Electric Heterogeneity Risk Score for Prediction of Sudden Cardiac Death in the General Population: The Atherosclerosis Risk in Communities (ARIC) and Cardiovascular Health (CHS) Studies. - Waks, Jonathan W; Sitlani, Colleen M; Soliman, Elsayed Z; Kabir, Muammar; Ghafoori, Elyar; Biggs, Mary L; Henrikson, Charles A; Sotoodehnia, Nona; Biering-Sørensen, Tor; Agarwal, Sunil K; Siscovick, David S; Post, Wendy S; et al. (Circulation, 2016)
BACKGROUND: Asymptomatic individuals account for the majority of sudden cardiac deaths (SCDs). Development of effective, low-cost, and noninvasive SCD risk stratification tools is necessary. METHODS AND RESULTS: Participants from the Atherosclerosis Risk in Communities study and Cardiovascular Health Study (n=20 177; age, 59.3±10.1 years; age range, 44-100 years; 56% female; 77% white) were followed up for 14.0 years (median). Five ECG markers of global electric heterogeneity (GEH; sum absolute QRST integral, spatial QRST angle, spatial ventricular gradient [SVG] magnitude, SVG elevation, and SVG azimuth) were measured on standard 12-lead ECGs. Cox proportional hazards and competing risks models evaluated associations between GEH electrocardiographic parameters and SCD. An SCD competing risks score was derived from demographics, comorbidities, and GEH parameters. SCD incidence was 1.86 per 1000 person-years. After multivariable adjustment, baseline GEH parameters and large increases in GEH parameters over time were independently associated with SCD. Final SCD risk scores included age, sex, race, diabetes mellitus, hypertension, coronary heart disease, stroke, and GEH parameters as continuous variables. When GEH parameters were added to clinical/demographic factors, the C statistic increased from 0.777 to 0.790 (P=0.008), the risk score classified 10-year SCD risk as high (>5%) in 7.2% of participants, 10% of SCD victims were appropriately reclassified into a high-risk category, and only 1.4% of SCD victims were inappropriately reclassified from high to intermediate risk. The net reclassification index was 18.3%. CONCLUSIONS: Abnormal electrophysiological substrate quantified by GEH parameters is independently associated with SCD in the general population. The addition of GEH parameters to clinical characteristics improves SCD risk prediction.

GWAS analysis of handgrip and lower body strength in older adults in the CHARGE consortium. - Matteini, Amy M; Tanaka, Toshiko; Karasik, David; Atzmon, Gil; Chou, Wen-Chi; Eicher, John D; Johnson, Andrew D; Arnold, Alice M; Callisaya, Michele L; Davies, Gail; Evans, Daniel S; Holtfreter, Birte; et al. (Aging Cell, 2016)
Decline in muscle strength with aging is an important predictor of health trajectory in the elderly. Several factors, including genetics, are proposed contributors to variability in muscle strength. To identify genetic contributors to muscle strength, a meta-analysis of genomewide association studies of handgrip was conducted. Grip strength was measured using a handheld dynamometer in 27 581 individuals of European descent over 65 years of age from 14 cohort studies. Genomewide association analysis was conducted on ~2.7 million imputed and genotyped variants (SNPs). Replication of the most significant findings was conducted using data from 6393 individuals from three cohorts. GWAS of lower body strength was also characterized in a subset of cohorts. Two genomewide significant (P-value< 5 × 10(-8) ) and 39 suggestive (P-value< 5 × 10(-5) ) associations were observed from meta-analysis of the discovery cohorts. After meta-analysis with replication cohorts, genomewide significant association was observed for rs752045 on chromosome 8 (β = 0.47, SE = 0.08, P-value = 5.20 × 10(-10) ). This SNP is mapped to an intergenic region and is located within an accessible chromatin region (DNase hypersensitivity site) in skeletal muscle myotubes differentiated from the human skeletal muscle myoblasts cell line. This locus alters a binding motif of the CCAAT/enhancer-binding protein-β (CEBPB) that is implicated in muscle repair mechanisms. GWAS of lower body strength did not yield significant results. A common genetic variant in a chromosomal region that regulates myotube differentiation and muscle repair may contribute to variability in grip strength in the elderly. Further studies are needed to uncover the mechanisms that link this genetic variant with muscle strength.

GWAS for executive function and processing speed suggests involvement of the CADM2 gene. - Ibrahim-Verbaas, C A; Bressler, J; Debette, S; Schuur, M; Smith, A V; Bis, J C; Davies, G; Trompet, S; Smith, J A; Wolf, C; Chibnik, L B; Liu, Y; et al. (Mol Psychiatry, 2016)
To identify common variants contributing to normal variation in two specific domains of cognitive functioning, we conducted a genome-wide association study (GWAS) of executive functioning and information processing speed in non-demented older adults from the CHARGE (Cohorts for Heart and Aging Research in Genomic Epidemiology) consortium. Neuropsychological testing was available for 5429-32,070 subjects of European ancestry aged 45 years or older, free of dementia and clinical stroke at the time of cognitive testing from 20 cohorts in the discovery phase. We analyzed performance on the Trail Making Test parts A and B, the Letter Digit Substitution Test (LDST), the Digit Symbol Substitution Task (DSST), semantic and phonemic fluency tests, and the Stroop Color and Word Test. Replication was sought in 1311-21860 subjects from 20 independent cohorts. A significant association was observed in the discovery cohorts for the single-nucleotide polymorphism (SNP) rs17518584 (discovery P-value=3.12 × 10(-8)) and in the joint discovery and replication meta-analysis (P-value=3.28 × 10(-9) after adjustment for age, gender and education) in an intron of the gene cell adhesion molecule 2 (CADM2) for performance on the LDST/DSST. Rs17518584 is located about 170 kb upstream of the transcription start site of the major transcript for the CADM2 gene, but is within an intron of a variant transcript that includes an alternative first exon. The variant is associated with expression of CADM2 in the cingulate cortex (P-value=4 × 10(-4)). The protein encoded by CADM2 is involved in glutamate signaling (P-value=7.22 × 10(-15)), gamma-aminobutyric acid (GABA) transport (P-value=1.36 × 10(-11)) and neuron cell-cell adhesion (P-value=1.48 × 10(-13)). Our findings suggest that genetic variation in the CADM2 gene is associated with individual differences in information processing speed.

Incident Atrial Fibrillation and Disability-Free Survival in the Cardiovascular Health Study. - Wallace, Erin R; Siscovick, David S; Sitlani, Colleen M; Dublin, Sascha; Mitchell, Pamela H; Odden, Michelle C; Hirsch, Calvin H; Thielke, Stephen; Heckbert, Susan R (J Am Geriatr Soc, 2016)
OBJECTIVES: To assess the associations between incident atrial fibrillation (AF) and disability-free survival and risk of disability. DESIGN: Prospective cohort study. SETTING: Cardiovascular Health Study. PARTICIPANTS: Individuals aged 65 and older and enrolled in fee-for-service Medicare followed between 1991 and 2009 (MN = 4,046). Individuals with prevalent AF, activity of daily living (ADL) disability, or a history of stroke or heart failure at baseline were excluded. MEASUREMENTS: Incident AF was identified according to annual study electrocardiogram, hospital discharge diagnosis, or Medicare claims. Disability-free survival was defined as survival free of ADL disability (any difficulty or inability in bathing, dressing, eating, using the toilet, walking around the home, or getting out of a bed or chair). ADLs were assessed at annual study visits or in a telephone interview. Association between incident AF and disability-free survival or risk of disability was estimated using Cox proportional hazards models. RESULTS: Over an average of 7.0 years of follow-up, 660 individuals (16.3%) developed incident AF, and 3,112 (77%) became disabled or died. Incident AF was associated with shorter disability-free survival (hazard ratio (HR) for death or ADL disability = 1.71, 95% confidence interval (CI) = 1.55-1.90) and a higher risk of ADL disability (HR = 1.36, 95% CI = 1.18-1.58) than in individuals with no history of AF. This association persisted after adjustment for interim stroke and heart failure. CONCLUSION: These results suggest that AF is a risk factor for shorter functional longevity in older adults, independent of other risk factors and comorbid conditions.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Atrial Fibrillation; Disability Evaluation; Electrocardiography; Female; Geriatric Assessment; Humans; Incidence; Longevity; Longitudinal Studies; Male; Medicare; Prevalence; Prospective Studies; Survival Rate; United States

Inflammatory markers and extent and progression of early atherosclerosis: Meta-analysis of individual-participant-data from 20 prospective studies of the PROG-IMT collaboration. - Willeit, Peter; Thompson, Simon G; Agewall, Stefan; Bergström, Göran; Bickel, Horst; Catapano, Alberico L; Chien, Kuo-Liong; de Groot, Eric; Empana, Jean-Philippe; Etgen, Thorleif; Franco, Oscar H; Iglseder, Bernhard; et al. (Eur J Prev Cardiol, 2016)
BACKGROUND: Large-scale epidemiological evidence on the role of inflammation in early atherosclerosis, assessed by carotid ultrasound, is lacking. We aimed to quantify cross-sectional and longitudinal associations of inflammatory markers with common-carotid-artery intima-media thickness (CCA-IMT) in the general population. METHODS: Information on high-sensitivity C-reactive protein, fibrinogen, leucocyte count and CCA-IMT was available in 20 prospective cohort studies of the PROG-IMT collaboration involving 49,097 participants free of pre-existing cardiovascular disease. Estimates of associations were calculated within each study and then combined using random-effects meta-analyses. RESULTS: Mean baseline CCA-IMT amounted to 0.74 mm (SD = 0.18) and mean CCA-IMT progression over a mean of 3.9 years to 0.011 mm/year (SD = 0.039). Cross-sectional analyses showed positive linear associations between inflammatory markers and baseline CCA-IMT. After adjustment for traditional cardiovascular risk factors, mean differences in baseline CCA-IMT per one-SD higher inflammatory marker were: 0.0082 mm for high-sensitivity C-reactive protein (p < 0.001); 0.0072 mm for fibrinogen (p < 0.001); and 0.0025 mm for leucocyte count (p = 0.033). 'Inflammatory load', defined as the number of elevated inflammatory markers (i.e. in upper two quintiles), showed a positive linear association with baseline CCA-IMT (p < 0.001). Longitudinal associations of baseline inflammatory markers and changes therein with CCA-IMT progression were null or at most weak. Participants with the highest 'inflammatory load' had a greater CCA-IMT progression (p = 0.015). CONCLUSION: Inflammation was independently associated with CCA-IMT cross-sectionally. The lack of clear associations with CCA-IMT progression may be explained by imprecision in its assessment within a limited time period. Our findings for 'inflammatory load' suggest important combined effects of the three inflammatory markers on early atherosclerosis.

Interaction of methylation-related genetic variants with circulating fatty acids on plasma lipids: a meta-analysis of 7 studies and methylation analysis of 3 studies in the Cohorts for Heart and Aging Research in Genomic Epidemiology consortium. - Ma, Yiyi; Follis, Jack L; Smith, Caren E; Tanaka, Toshiko; Manichaikul, Ani W; Chu, Audrey Y; Samieri, Cecilia; Zhou, Xia; Guan, Weihua; Wang, Lu; Biggs, Mary L; Chen, Yii-der I; et al. (Am J Clin Nutr, 2016)
BACKGROUND: DNA methylation is influenced by diet and single nucleotide polymorphisms (SNPs), and methylation modulates gene expression. OBJECTIVE: We aimed to explore whether the gene-by-diet interactions on blood lipids act through DNA methylation. DESIGN: We selected 7 SNPs on the basis of predicted relations in fatty acids, methylation, and lipids. We conducted a meta-analysis and a methylation and mediation analysis with the use of data from the CHARGE (Cohorts for Heart and Aging Research in Genomic Epidemiology) consortium and the ENCODE (Encyclopedia of DNA Elements) consortium. RESULTS: On the basis of the meta-analysis of 7 cohorts in the CHARGE consortium, higher plasma HDL cholesterol was associated with fewer C alleles at ATP-binding cassette subfamily A member 1 (ABCA1) rs2246293 (β = -0.6 mg/dL, P = 0.015) and higher circulating eicosapentaenoic acid (EPA) (β = 3.87 mg/dL, P = 5.62 × 10(21)). The difference in HDL cholesterol associated with higher circulating EPA was dependent on genotypes at rs2246293, and it was greater for each additional C allele (β = 1.69 mg/dL, P = 0.006). In the GOLDN (Genetics of Lipid Lowering Drugs and Diet Network) study, higher ABCA1 promoter cg14019050 methylation was associated with more C alleles at rs2246293 (β = 8.84%, P = 3.51 × 10(18)) and lower circulating EPA (β = -1.46%, P = 0.009), and the mean difference in methylation of cg14019050 that was associated with higher EPA was smaller with each additional C allele of rs2246293 (β = -2.83%, P = 0.007). Higher ABCA1 cg14019050 methylation was correlated with lower ABCA1 expression (r = -0.61, P = 0.009) in the ENCODE consortium and lower plasma HDL cholesterol in the GOLDN study (r = -0.12, P = 0.0002). An additional mediation analysis was meta-analyzed across the GOLDN study, Cardiovascular Health Study, and the Multi-Ethnic Study of Atherosclerosis. Compared with the model without the adjustment of cg14019050 methylation, the model with such adjustment provided smaller estimates of the mean plasma HDL cholesterol concentration in association with both the rs2246293 C allele and EPA and a smaller difference by rs2246293 genotypes in the EPA-associated HDL cholesterol. However, the differences between 2 nested models were NS (P > 0.05). CONCLUSION: We obtained little evidence that the gene-by-fatty acid interactions on blood lipids act through DNA methylation.
Keywords: Apolipoproteins E; ATP Binding Cassette Transporter 1; Cholesterol, HDL; Cohort Studies; Diet; DNA Methylation; Eicosapentaenoic Acid; Epigenesis, Genetic; Fatty Acids; Gene Expression Regulation; Humans; Lipids; Polymorphism, Single Nucleotide; Promoter Regions, Genetic; Triglycerides

KLB is associated with alcohol drinking, and its gene product β-Klotho is necessary for FGF21 regulation of alcohol preference. - Schumann, Gunter; Liu, Chunyu; O'Reilly, Paul; Gao, He; Song, Parkyong; Xu, Bing; Ruggeri, Barbara; Amin, Najaf; Jia, Tianye; Preis, Sarah; Segura Lepe, Marcelo; Akira, Shizuo; et al. (Proc Natl Acad Sci U S A, 2016)
Excessive alcohol consumption is a major public health problem worldwide. Although drinking habits are known to be inherited, few genes have been identified that are robustly linked to alcohol drinking. We conducted a genome-wide association metaanalysis and replication study among >105,000 individuals of European ancestry and identified β-Klotho (KLB) as a locus associated with alcohol consumption (rs11940694; P = 9.2 × 10(-12)). β-Klotho is an obligate coreceptor for the hormone FGF21, which is secreted from the liver and implicated in macronutrient preference in humans. We show that brain-specific β-Klotho KO mice have an increased alcohol preference and that FGF21 inhibits alcohol drinking by acting on the brain. These data suggest that a liver-brain endocrine axis may play an important role in the regulation of alcohol drinking behavior and provide a unique pharmacologic target for reducing alcohol consumption.

Large-Scale Exome-wide Association Analysis Identifies Loci for White Blood Cell Traits and Pleiotropy with Immune-Mediated Diseases. - Tajuddin, Salman M; Schick, Ursula M; Eicher, John D; Chami, Nathalie; Giri, Ayush; Brody, Jennifer A; Hill, W David; Kacprowski, Tim; Li, Jin; Lyytikäinen, Leo-Pekka; Manichaikul, Ani; Mihailov, Evelin; et al. (Am J Hum Genet, 2016)
White blood cells play diverse roles in innate and adaptive immunity. Genetic association analyses of phenotypic variation in circulating white blood cell (WBC) counts from large samples of otherwise healthy individuals can provide insights into genes and biologic pathways involved in production, differentiation, or clearance of particular WBC lineages (myeloid, lymphoid) and also potentially inform the genetic basis of autoimmune, allergic, and blood diseases. We performed an exome array-based meta-analysis of total WBC and subtype counts (neutrophils, monocytes, lymphocytes, basophils, and eosinophils) in a multi-ancestry discovery and replication sample of ∼157,622 individuals from 25 studies. We identified 16 common variants (8 of which were coding variants) associated with one or more WBC traits, the majority of which are pleiotropically associated with autoimmune diseases. Based on functional annotation, these loci included genes encoding surface markers of myeloid, lymphoid, or hematopoietic stem cell differentiation (CD69, CD33, CD87), transcription factors regulating lineage specification during hematopoiesis (ASXL1, IRF8, IKZF1, JMJD1C, ETS2-PSMG1), and molecules involved in neutrophil clearance/apoptosis (C10orf54, LTA), adhesion (TNXB), or centrosome and microtubule structure/function (KIF9, TUBD1). Together with recent reports of somatic ASXL1 mutations among individuals with idiopathic cytopenias or clonal hematopoiesis of undetermined significance, the identification of a common regulatory 3' UTR variant of ASXL1 suggests that both germline and somatic ASXL1 mutations contribute to lower blood counts in otherwise asymptomatic individuals. These association results shed light on genetic mechanisms that regulate circulating WBC counts and suggest a prominent shared genetic architecture with inflammatory and autoimmune diseases.

Large-scale pharmacogenomic study of sulfonylureas and the QT, JT and QRS intervals: CHARGE Pharmacogenomics Working Group. - Floyd, J S; Sitlani, C M; Avery, C L; Noordam, R; Li, X; Smith, A V; Gogarten, S M; Li, J; Broer, L; Evans, D S; Trompet, S; Brody, J A; et al. (Pharmacogenomics J, 2016)
Sulfonylureas, a commonly used class of medication used to treat type 2 diabetes, have been associated with an increased risk of cardiovascular disease. Their effects on QT interval duration and related electrocardiographic phenotypes are potential mechanisms for this adverse effect. In 11 ethnically diverse cohorts that included 71 857 European, African-American and Hispanic/Latino ancestry individuals with repeated measures of medication use and electrocardiogram (ECG) measurements, we conducted a pharmacogenomic genome-wide association study of sulfonylurea use and three ECG phenotypes: QT, JT and QRS intervals. In ancestry-specific meta-analyses, eight novel pharmacogenomic loci met the threshold for genome-wide significance (P<5 × 10(-8)), and a pharmacokinetic variant in CYP2C9 (rs1057910) that has been associated with sulfonylurea-related treatment effects and other adverse drug reactions in previous studies was replicated. Additional research is needed to replicate the novel findings and to understand their biological basis.The Pharmacogenomics Journal advance online publication, 13 December 2016; doi:10.1038/tpj.2016.90.

Meta-analysis identifies common and rare variants influencing blood pressure and overlapping with metabolic trait loci. - Liu, Chunyu; Kraja, Aldi T; Smith, Jennifer A; Brody, Jennifer A; Franceschini, Nora; Bis, Joshua C; Rice, Kenneth; Morrison, Alanna C; Lu, Yingchang; Weiss, Stefan; Guo, Xiuqing; Palmas, Walter; et al. (Nat Genet, 2016)
Meta-analyses of association results for blood pressure using exome-centric single-variant and gene-based tests identified 31 new loci in a discovery stage among 146,562 individuals, with follow-up and meta-analysis in 180,726 additional individuals (total n = 327,288). These blood pressure-associated loci are enriched for known variants for cardiometabolic traits. Associations were also observed for the aggregation of rare and low-frequency missense variants in three genes, NPR1, DBH, and PTPMT1. In addition, blood pressure associations at 39 previously reported loci were confirmed. The identified variants implicate biological pathways related to cardiometabolic traits, vascular function, and development. Several new variants are inferred to have roles in transcription or as hubs in protein-protein interaction networks. Genetic risk scores constructed from the identified variants were strongly associated with coronary disease and myocardial infarction. This large collection of blood pressure-associated loci suggests new therapeutic strategies for hypertension, emphasizing a link with cardiometabolic risk.

A meta-analysis of 120 246 individuals identifies 18 new loci for fibrinogen concentration. - de Vries, Paul S; Chasman, Daniel I; Sabater-Lleal, Maria; Chen, Ming-Huei; Huffman, Jennifer E; Steri, Maristella; Tang, Weihong; Teumer, Alexander; Marioni, Riccardo E; Grossmann, Vera; Hottenga, Jouke J; Trompet, Stella; et al. (Hum Mol Genet, 2016)
Genome-wide association studies have previously identified 23 genetic loci associated with circulating fibrinogen concentration. These studies used HapMap imputation and did not examine the X-chromosome. 1000 Genomes imputation provides better coverage of uncommon variants, and includes indels. We conducted a genome-wide association analysis of 34 studies imputed to the 1000 Genomes Project reference panel and including ∼120 000 participants of European ancestry (95 806 participants with data on the X-chromosome). Approximately 10.7 million single-nucleotide polymorphisms and 1.2 million indels were examined. We identified 41 genome-wide significant fibrinogen loci; of which, 18 were newly identified. There were no genome-wide significant signals on the X-chromosome. The lead variants of five significant loci were indels. We further identified six additional independent signals, including three rare variants, at two previously characterized loci: FGB and IRF1. Together the 41 loci explain 3% of the variance in plasma fibrinogen concentration.

Meta-analysis of 49 549 individuals imputed with the 1000 Genomes Project reveals an exonic damaging variant in ANGPTL4 determining fasting TG levels. - van Leeuwen, Elisabeth M; Sabo, Aniko; Bis, Joshua C; Huffman, Jennifer E; Manichaikul, Ani; Smith, Albert V; Feitosa, Mary F; Demissie, Serkalem; Joshi, Peter K; Duan, Qing; Marten, Jonathan; van Klinken, Jan B; et al. (J Med Genet, 2016)
BACKGROUND: So far, more than 170 loci have been associated with circulating lipid levels through genome-wide association studies (GWAS). These associations are largely driven by common variants, their function is often not known, and many are likely to be markers for the causal variants. In this study we aimed to identify more new rare and low-frequency functional variants associated with circulating lipid levels. METHODS: We used the 1000 Genomes Project as a reference panel for the imputations of GWAS data from ∼60 000 individuals in the discovery stage and ∼90 000 samples in the replication stage. RESULTS: Our study resulted in the identification of five new associations with circulating lipid levels at four loci. All four loci are within genes that can be linked biologically to lipid metabolism. One of the variants, rs116843064, is a damaging missense variant within the ANGPTL4 gene. CONCLUSIONS: This study illustrates that GWAS with high-scale imputation may still help us unravel the biological mechanism behind circulating lipid levels.

Meta-analysis of genome-wide association studies of HDL cholesterol response to statins. - Postmus, Iris; Warren, Helen R; Trompet, Stella; Arsenault, Benoit J; Avery, Christy L; Bis, Joshua C; Chasman, Daniel I; de Keyser, Catherine E; Deshmukh, Harshal A; Evans, Daniel S; Feng, QiPing; Li, Xiaohui; et al. (J Med Genet, 2016)
BACKGROUND: In addition to lowering low density lipoprotein cholesterol (LDL-C), statin therapy also raises high density lipoprotein cholesterol (HDL-C) levels. Inter-individual variation in HDL-C response to statins may be partially explained by genetic variation. METHODS AND RESULTS: We performed a meta-analysis of genome-wide association studies (GWAS) to identify variants with an effect on statin-induced high density lipoprotein cholesterol (HDL-C) changes. The 123 most promising signals with p<1×10(-4) from the 16 769 statin-treated participants in the first analysis stage were followed up in an independent group of 10 951 statin-treated individuals, providing a total sample size of 27 720 individuals. The only associations of genome-wide significance (p<5×10(-8)) were between minor alleles at the CETP locus and greater HDL-C response to statin treatment. CONCLUSIONS: Based on results from this study that included a relatively large sample size, we suggest that CETP may be the only detectable locus with common genetic variants that influence HDL-C response to statins substantially in individuals of European descent. Although CETP is known to be associated with HDL-C, we provide evidence that this pharmacogenetic effect is independent of its association with baseline HDL-C levels.

Multiethnic Exome-Wide Association Study of Subclinical Atherosclerosis. - Natarajan, Pradeep; Bis, Joshua C; Bielak, Lawrence F; Cox, Amanda J; Dörr, Marcus; Feitosa, Mary F; Franceschini, Nora; Guo, Xiuqing; Hwang, Shih-Jen; Isaacs, Aaron; Jhun, Min A; Kavousi, Maryam; et al. (Circ Cardiovasc Genet, 2016)
BACKGROUND: -The burden of subclinical atherosclerosis in asymptomatic individuals is heritable and associated with elevated risk of developing clinical coronary heart disease (CHD). We sought to identify genetic variants in protein-coding regions associated with subclinical atherosclerosis and the risk of subsequent CHD. METHODS AND RESULTS: -We studied a total of 25,109 European ancestry and African-American participants with coronary artery calcification (CAC) measured by cardiac computed tomography and 52,869 with common carotid intima media thickness (CIMT) measured by ultrasonography within the Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) Consortium. Participants were genotyped for 247,870 DNA sequence variants (231,539 in exons) across the genome. A meta-analysis of exome-wide association studies was performed across cohorts for CAC and CIMT. APOB p.Arg3527Gln was associated with four-fold excess CAC (P = 3×10(-10)). The APOE ε2 allele (p.Arg176Cys) was associated with both 22.3% reduced CAC (P = 1×10(-12)) and 1.4% reduced CIMT (P = 4×10(-14)) in carriers compared with non-carriers. In secondary analyses conditioning on LDL cholesterol concentration, the ε2 protective association with CAC, although attenuated, remained strongly significant. Additionally, the presence of ε2 was associated with reduced risk for CHD (OR 0.77; P = 1×10(-11)). CONCLUSIONS: -Exome-wide association meta-analysis demonstrates that protein-coding variants in APOB and APOE associate with subclinical atherosclerosis. APOE ε2 represents the first significant association for multiple subclinical atherosclerosis traits across multiple ethnicities as well as clinical CHD.

Natriuretic peptides and integrated risk assessment for cardiovascular disease: an individual-participant-data meta-analysis. - Willeit, Peter; Kaptoge, Stephen; Welsh, Paul; Butterworth, Adam; Chowdhury, Rajiv; Spackman, Sarah; Pennells, Lisa; Gao, Pei; Burgess, Stephen; Freitag, Daniel; Sweeting, Michael; Wood, Angela; et al. (Lancet Diabetes Endocrinol, 2016)
BACKGROUND: Guidelines for primary prevention of cardiovascular diseases focus on prediction of coronary heart disease and stroke. We assessed whether or not measurement of N-terminal-pro-B-type natriuretic peptide (NT-proBNP) concentration could enable a more integrated approach than at present by predicting heart failure and enhancing coronary heart disease and stroke risk assessment. METHODS: In this individual-participant-data meta-analysis, we generated and harmonised individual-participant data from relevant prospective studies via both de-novo NT-proBNP concentration measurement of stored samples and collection of data from studies identified through a systematic search of the literature (PubMed, Scientific Citation Index Expanded, and Embase) for articles published up to Sept 4, 2014, using search terms related to natriuretic peptide family members and the primary outcomes, with no language restrictions. We calculated risk ratios and measures of risk discrimination and reclassification across predicted 10 year risk categories (ie, <5%, 5% to <7·5%, and ≥7·5%), adding assessment of NT-proBNP concentration to that of conventional risk factors (ie, age, sex, smoking status, systolic blood pressure, history of diabetes, and total and HDL cholesterol concentrations). Primary outcomes were the combination of coronary heart disease and stroke, and the combination of coronary heart disease, stroke, and heart failure. FINDINGS: We recorded 5500 coronary heart disease, 4002 stroke, and 2212 heart failure outcomes among 95 617 participants without a history of cardiovascular disease in 40 prospective studies. Risk ratios (for a comparison of the top third vs bottom third of NT-proBNP concentrations, adjusted for conventional risk factors) were 1·76 (95% CI 1·56-1·98) for the combination of coronary heart disease and stroke and 2·00 (1·77-2·26) for the combination of coronary heart disease, stroke, and heart failure. Addition of information about NT-proBNP concentration to a model containing conventional risk factors was associated with a C-index increase of 0·012 (0·010-0·014) and a net reclassification improvement of 0·027 (0·019-0·036) for the combination of coronary heart disease and stroke and a C-index increase of 0·019 (0·016-0·022) and a net reclassification improvement of 0·028 (0·019-0·038) for the combination of coronary heart disease, stroke, and heart failure. INTERPRETATION: In people without baseline cardiovascular disease, NT-proBNP concentration assessment strongly predicted first-onset heart failure and augmented coronary heart disease and stroke prediction, suggesting that NT-proBNP concentration assessment could be used to integrate heart failure into cardiovascular disease primary prevention. FUNDING: British Heart Foundation, Austrian Science Fund, UK Medical Research Council, National Institute for Health Research, European Research Council, and European Commission Framework Programme 7.
Keywords: Aged; Biomarkers; Cardiovascular Diseases; Female; Humans; Male; Middle Aged; Natriuretic Peptide, Brain; Peptide Fragments; Prospective Studies; Risk Assessment

A novel Alzheimer disease locus located near the gene encoding tau protein. - Jun, G; Ibrahim-Verbaas, C A; Vronskaya, M; Lambert, J-C; Chung, J; Naj, A C; Kunkle, B W; Wang, L-S; Bis, J C; Bellenguez, C; Harold, D; Lunetta, K L; et al. (Mol Psychiatry, 2016)
APOE ɛ4, the most significant genetic risk factor for Alzheimer disease (AD), may mask effects of other loci. We re-analyzed genome-wide association study (GWAS) data from the International Genomics of Alzheimer's Project (IGAP) Consortium in APOE ɛ4+ (10 352 cases and 9207 controls) and APOE ɛ4- (7184 cases and 26 968 controls) subgroups as well as in the total sample testing for interaction between a single-nucleotide polymorphism (SNP) and APOE ɛ4 status. Suggestive associations (P<1 × 10(-4)) in stage 1 were evaluated in an independent sample (stage 2) containing 4203 subjects (APOE ɛ4+: 1250 cases and 536 controls; APOE ɛ4-: 718 cases and 1699 controls). Among APOE ɛ4- subjects, novel genome-wide significant (GWS) association was observed with 17 SNPs (all between KANSL1 and LRRC37A on chromosome 17 near MAPT) in a meta-analysis of the stage 1 and stage 2 data sets (best SNP, rs2732703, P=5·8 × 10(-9)). Conditional analysis revealed that rs2732703 accounted for association signals in the entire 100-kilobase region that includes MAPT. Except for previously identified AD loci showing stronger association in APOE ɛ4+ subjects (CR1 and CLU) or APOE ɛ4- subjects (MS4A6A/MS4A4A/MS4A6E), no other SNPs were significantly associated with AD in a specific APOE genotype subgroup. In addition, the finding in the stage 1 sample that AD risk is significantly influenced by the interaction of APOE with rs1595014 in TMEM106B (P=1·6 × 10(-7)) is noteworthy, because TMEM106B variants have previously been associated with risk of frontotemporal dementia. Expression quantitative trait locus analysis revealed that rs113986870, one of the GWS SNPs near rs2732703, is significantly associated with four KANSL1 probes that target transcription of the first translated exon and an untranslated exon in hippocampus (P ⩽ 1.3 × 10(-8)), frontal cortex (P ⩽ 1.3 × 10(-9)) and temporal cortex (P⩽1.2 × 10(-11)). Rs113986870 is also strongly associated with a MAPT probe that targets transcription of alternatively spliced exon 3 in frontal cortex (P=9.2 × 10(-6)) and temporal cortex (P=2.6 × 10(-6)). Our APOE-stratified GWAS is the first to show GWS association for AD with SNPs in the chromosome 17q21.31 region. Replication of this finding in independent samples is needed to verify that SNPs in this region have significantly stronger effects on AD risk in persons lacking APOE ɛ4 compared with persons carrying this allele, and if this is found to hold, further examination of this region and studies aimed at deciphering the mechanism(s) are warranted.
Keywords: Alzheimer Disease; Apolipoprotein E4; Chromosomes, Human, Pair 17; Genome-Wide Association Study; Humans; Polymorphism, Single Nucleotide; tau Proteins

Novel Genetic Loci Associated With Retinal Microvascular Diameter. - Jensen, Richard A; Sim, Xueling; Smith, Albert Vernon; Li, Xiaohui; Jakobsdottir, Johanna; Cheng, Ching-Yu; Brody, Jennifer A; Cotch, Mary Frances; McKnight, Barbara; Klein, Ronald; Wang, Jie Jin; Kifley, Annette; et al. (Circ Cardiovasc Genet, 2016)
BACKGROUND: There is increasing evidence that retinal microvascular diameters are associated with cardiovascular and cerebrovascular conditions. The shared genetic effects of these associations are currently unknown. The aim of this study was to increase our understanding of the genetic factors that mediate retinal vessel size. METHODS AND RESULTS: This study extends previous genome-wide association study results using 24 000+ multiethnic participants from 7 discovery cohorts and 5000+ subjects of European ancestry from 2 replication cohorts. Using the Illumina HumanExome BeadChip, we investigate the association of single-nucleotide polymorphisms and variants collectively across genes with summary measures of retinal vessel diameters, referred to as the central retinal venule equivalent and the central retinal arteriole equivalent. We report 4 new loci associated with central retinal venule equivalent, one of which is also associated with central retinal arteriole equivalent. The 4 single-nucleotide polymorphisms are rs7926971 in TEAD1 (P=3.1×10(-) (11); minor allele frequency=0.43), rs201259422 in TSPAN10 (P=4.4×10(-9); minor allele frequency=0.27), rs5442 in GNB3 (P=7.0×10(-10); minor allele frequency=0.05), and rs1800407 in OCA2 (P=3.4×10(-8); minor allele frequency=0.05). The latter single-nucleotide polymorphism, rs1800407, was also associated with central retinal arteriole equivalent (P=6.5×10(-12)). Results from the gene-based burden tests were null. In phenotype look-ups, single-nucleotide polymorphism rs201255422 was associated with both systolic (P=0.001) and diastolic blood pressures (P=8.3×10(-04)). CONCLUSIONS: Our study expands the understanding of genetic factors influencing the size of the retinal microvasculature. These findings may also provide insight into the relationship between retinal and systemic microvascular disease.

{Novel genetic loci underlying human intracranial volume identified through genome-wide association - Adams, H. H.; Hibar, D. P.; Chouraki, V.; Stein, J. L.; Nyquist, P. A.; Renter?a, M. E.; Trompet, S.; Arias-Vasquez, A.; Seshadri, S.; Desrivi?res, S.; Beecham, A. H.; Jahanshad, N.; et al. (Nat Neurosci, 2016)
Intracranial volume reflects the maximally attained brain size during development, and remains stable with loss of tissue in late life. It is highly heritable, but the underlying genes remain largely undetermined. In a genome-wide association study of 32,438 adults, we discovered five previously unknown loci for intracranial volume and confirmed two known signals. Four of the loci were also associated with adult human stature, but these remained associated with intracranial volume after adjusting for height. We found a high genetic correlation with child head circumference (Ïgenetic = 0.748), which indicates a similar genetic background and allowed us to identify four additional loci through meta-analysis (Ncombined = 37,345). Variants for intracranial volume were also related to childhood and adult cognitive function, and Parkinson's disease, and were enriched near genes involved in growth pathways, including PI3K-AKT signaling. These findings identify the biological underpinnings of intracranial volume and their link to physiological and pathological traits.

Platelet-Related Variants Identified by Exomechip Meta-analysis in 157,293 Individuals. - Eicher, John D; Chami, Nathalie; Kacprowski, Tim; Nomura, Akihiro; Chen, Ming-Huei; Yanek, Lisa R; Tajuddin, Salman M; Schick, Ursula M; Slater, Andrew J; Pankratz, Nathan; Polfus, Linda; Schurmann, Claudia; et al. (Am J Hum Genet, 2016)
Platelet production, maintenance, and clearance are tightly controlled processes indicative of platelets' important roles in hemostasis and thrombosis. Platelets are common targets for primary and secondary prevention of several conditions. They are monitored clinically by complete blood counts, specifically with measurements of platelet count (PLT) and mean platelet volume (MPV). Identifying genetic effects on PLT and MPV can provide mechanistic insights into platelet biology and their role in disease. Therefore, we formed the Blood Cell Consortium (BCX) to perform a large-scale meta-analysis of Exomechip association results for PLT and MPV in 157,293 and 57,617 individuals, respectively. Using the low-frequency/rare coding variant-enriched Exomechip genotyping array, we sought to identify genetic variants associated with PLT and MPV. In addition to confirming 47 known PLT and 20 known MPV associations, we identified 32 PLT and 18 MPV associations not previously observed in the literature across the allele frequency spectrum, including rare large effect (FCER1A), low-frequency (IQGAP2, MAP1A, LY75), and common (ZMIZ2, SMG6, PEAR1, ARFGAP3/PACSIN2) variants. Several variants associated with PLT/MPV (PEAR1, MRVI1, PTGES3) were also associated with platelet reactivity. In concurrent BCX analyses, there was overlap of platelet-associated variants with red (MAP1A, TMPRSS6, ZMIZ2) and white (PEAR1, ZMIZ2, LY75) blood cell traits, suggesting common regulatory pathways with shared genetic architecture among these hematopoietic lineages. Our large-scale Exomechip analyses identified previously undocumented associations with platelet traits and further indicate that several complex quantitative hematological, lipid, and cardiovascular traits share genetic factors.

A principal component meta-analysis on multiple anthropometric traits identifies novel loci for body shape. - Ried, Janina S; Jeff M, Janina; Chu, Audrey Y; Bragg-Gresham, Jennifer L; van Dongen, Jenny; Huffman, Jennifer E; Ahluwalia, Tarunveer S; Cadby, Gemma; Eklund, Niina; Eriksson, Joel; Esko, Tõnu; Feitosa, Mary F; et al. (Nat Commun, 2016)
Large consortia have revealed hundreds of genetic loci associated with anthropometric traits, one trait at a time. We examined whether genetic variants affect body shape as a composite phenotype that is represented by a combination of anthropometric traits. We developed an approach that calculates averaged PCs (AvPCs) representing body shape derived from six anthropometric traits (body mass index, height, weight, waist and hip circumference, waist-to-hip ratio). The first four AvPCs explain >99% of the variability, are heritable, and associate with cardiometabolic outcomes. We performed genome-wide association analyses for each body shape composite phenotype across 65 studies and meta-analysed summary statistics. We identify six novel loci: LEMD2 and CD47 for AvPC1, RPS6KA5/C14orf159 and GANAB for AvPC3, and ARL15 and ANP32 for AvPC4. Our findings highlight the value of using multiple traits to define complex phenotypes for discovery, which are not captured by single-trait analyses, and may shed light onto new pathways.
Keywords: Anthropometry; Body Size; Genome-Wide Association Study; Genotype; Humans; Models, Genetic; Principal Component Analysis

Rare Functional Variant in TM2D3 is Associated with Late-Onset Alzheimer's Disease. - Jakobsdottir, Johanna; van der Lee, Sven J; Bis, Joshua C; Chouraki, Vincent; Li-Kroeger, David; Yamamoto, Shinya; Grove, Megan L; Naj, Adam; Vronskaya, Maria; Salazar, Jose L; DeStefano, Anita L; Brody, Jennifer A; et al. (PLoS Genet, 2016)
We performed an exome-wide association analysis in 1393 late-onset Alzheimer's disease (LOAD) cases and 8141 controls from the CHARGE consortium. We found that a rare variant (P155L) in TM2D3 was enriched in Icelanders (~0.5% versus <0.05% in other European populations). In 433 LOAD cases and 3903 controls from the Icelandic AGES sub-study, P155L was associated with increased risk and earlier onset of LOAD [odds ratio (95% CI) = 7.5 (3.5-15.9), p = 6.6x10-9]. Mutation in the Drosophila TM2D3 homolog, almondex, causes a phenotype similar to loss of Notch/Presenilin signaling. Human TM2D3 is capable of rescuing these phenotypes, but this activity is abolished by P155L, establishing it as a functionally damaging allele. Our results establish a rare TM2D3 variant in association with LOAD susceptibility, and together with prior work suggests possible links to the β-amyloid cascade.

Rare, low frequency and common coding variants in CHRNA5 and their contribution to nicotine dependence in European and African Americans. - Olfson, E; Saccone, N L; Johnson, E O; Chen, L-S; Culverhouse, R; Doheny, K; Foltz, S M; Fox, L; Gogarten, S M; Hartz, S; Hetrick, K; Laurie, C C; et al. (Mol Psychiatry, 2016)
The common nonsynonymous variant rs16969968 in the α5 nicotinic receptor subunit gene (CHRNA5) is the strongest genetic risk factor for nicotine dependence in European Americans and contributes to risk in African Americans. To comprehensively examine whether other CHRNA5 coding variation influences nicotine dependence risk, we performed targeted sequencing on 1582 nicotine-dependent cases (Fagerström Test for Nicotine Dependence score⩾4) and 1238 non-dependent controls, with independent replication of common and low frequency variants using 12 studies with exome chip data. Nicotine dependence was examined using logistic regression with individual common variants (minor allele frequency (MAF)⩾0.05), aggregate low frequency variants (0.05>MAF⩾0.005) and aggregate rare variants (MAF<0.005). Meta-analysis of primary results was performed with replication studies containing 12 174 heavy and 11 290 light smokers. Next-generation sequencing with 180 × coverage identified 24 nonsynonymous variants and 2 frameshift deletions in CHRNA5, including 9 novel variants in the 2820 subjects. Meta-analysis confirmed the risk effect of the only common variant (rs16969968, European ancestry: odds ratio (OR)=1.3, P=3.5 × 10(-11); African ancestry: OR=1.3, P=0.01) and demonstrated that three low frequency variants contributed an independent risk (aggregate term, European ancestry: OR=1.3, P=0.005; African ancestry: OR=1.4, P=0.0006). The remaining 22 rare coding variants were associated with increased risk of nicotine dependence in the European American primary sample (OR=12.9, P=0.01) and in the same risk direction in African Americans (OR=1.5, P=0.37). Our results indicate that common, low frequency and rare CHRNA5 coding variants are independently associated with nicotine dependence risk. These newly identified variants likely influence the risk for smoking-related diseases such as lung cancer.

Rooted in risk: genetic predisposition for low-density lipoprotein cholesterol level associates with diminished low-density lipoprotein cholesterol response to statin treatment. - Smit, Roelof Aj; Postmus, Iris; Trompet, Stella; Barnes, Michael R; Warren, Helen; Arsenault, Benoit J; Chasman, Daniel I; Cupples, L Adrienne; Hitman, Graham A; Krauss, Ronald M; Li, Xiaohui; Psaty, Bruce M; et al. (Pharmacogenomics, 2016)
AIMS: To utilize previously reported lead SNPs for low-density lipoprotein cholesterol (LDL-c) levels to find additional loci of importance to statin response, and examine whether genetic predisposition to LDL-c levels associates with differential statin response. METHODS: We investigated effects on statin response of 59 LDL-c SNPs, by combining summary level statistics from the Global Lipids Genetics and Genomic Investigation of Statin Therapy consortia. RESULTS: Lead SNPs for APOE, SORT1 and NPC1L1 were associated with a decreased LDL-c response to statin treatment, as was overall genetic predisposition for increased LDL-c levels as quantified with 59 SNPs, with a 5.4% smaller statin response per standard deviation increase in genetically raised LDL-c levels. CONCLUSION: Genetic predisposition for increased LDL-c level may decrease efficacy of statin therapy.
Keywords: Cholesterol, LDL; Genetic Predisposition to Disease; Humans; Hydroxymethylglutaryl-CoA Reductase Inhibitors; Pharmacogenetics; Polymorphism, Single Nucleotide; Triglycerides

SOS2 and ACP1 Loci Identified through Large-Scale Exome Chip Analysis Regulate Kidney Development and Function. - Li, Man; Li, Yong; Weeks, Olivia; Mijatovic, Vladan; Teumer, Alexander; Huffman, Jennifer E; Tromp, Gerard; Fuchsberger, Christian; Gorski, Mathias; Lyytikäinen, Leo-Pekka; Nutile, Teresa; Sedaghat, Sanaz; et al. (J Am Soc Nephrol, 2016)
Genome-wide association studies have identified >50 common variants associated with kidney function, but these variants do not fully explain the variation in eGFR. We performed a two-stage meta-analysis of associations between genotypes from the Illumina exome array and eGFR on the basis of serum creatinine (eGFRcrea) among participants of European ancestry from the CKDGen Consortium (nStage1: 111,666; nStage2: 48,343). In single-variant analyses, we identified single nucleotide polymorphisms at seven new loci associated with eGFRcrea (PPM1J, EDEM3, ACP1, SPEG, EYA4, CYP1A1, and ATXN2L; PStage1<3.7×10(-7)), of which most were common and annotated as nonsynonymous variants. Gene-based analysis identified associations of functional rare variants in three genes with eGFRcrea, including a novel association with the SOS Ras/Rho guanine nucleotide exchange factor 2 gene, SOS2 (P=5.4×10(-8) by sequence kernel association test). Experimental follow-up in zebrafish embryos revealed changes in glomerular gene expression and renal tubule morphology in the embryonic kidney of acp1- and sos2-knockdowns. These developmental abnormalities associated with altered blood clearance rate and heightened prevalence of edema. This study expands the number of loci associated with kidney function and identifies novel genes with potential roles in kidney formation.

Thyroid Function Within the Reference Range and the Risk of Stroke: An Individual Participant Data Analysis. - Chaker, Layal; Baumgartner, Christine; den Elzen, Wendy P J; Collet, Tinh-Hai; Ikram, M Arfan; Blum, Manuel R; Dehghan, Abbas; Drechsler, Christiane; Luben, Robert N; Portegies, Marileen L P; Iervasi, Giorgio; Medici, Marco; et al. (J Clin Endocrinol Metab, 2016)
CONTEXT: The currently applied reference ranges for thyroid function are under debate. Despite evidence that thyroid function within the reference range is related with several cardiovascular disorders, its association with the risk of stroke has not been evaluated previously. DESIGN AND SETTING: We identified studies through a systematic literature search and the Thyroid Studies Collaboration, a collaboration of prospective cohort studies. Studies measuring baseline TSH, free T4, and stroke outcomes were included, and we collected individual participant data from each study, including thyroid function measurements and incident all stroke (combined fatal and nonfatal) and fatal stroke. The applied reference range for TSH levels was between 0.45 and 4.49 mIU/L. RESULTS: We collected individual participant data on 43 598 adults with TSH within the reference range from 17 cohorts, with a median follow-up of 11.6 years (interquartile range 5.1-13.9), including 449 908 person-years. Age- and sex-adjusted pooled hazard ratio for TSH was 0.78 (95% confidence interval [CI] 0.65-0.95 across the reference range of TSH) for all stroke and 0.83 (95% CI 0.62-1.09) for fatal stroke. For the free T4 analyses, the hazard ratio was 1.08 (95% CI 0.99-1.15 per SD increase) for all stroke and 1.10 (95% CI 1.04-1.19) for fatal stroke. This was independent of cardiovascular risk factors including systolic blood pressure, total cholesterol, smoking, and prevalent diabetes. CONCLUSION: Higher levels of TSH within the reference range may decrease the risk of stroke, highlighting the need for further research focusing on the clinical consequences associated with differences within the reference range of thyroid function.

Trans-ethnic Meta-analysis and Functional Annotation Illuminates the Genetic Architecture of Fasting Glucose and Insulin. - Liu, Ching-Ti; Raghavan, Sridharan; Maruthur, Nisa; Kabagambe, Edmond Kato; Hong, Jaeyoung; Ng, Maggie C Y; Hivert, Marie-France; Lu, Yingchang; An, Ping; Bentley, Amy R; Drolet, Anne M; Gaulton, Kyle J; et al. (Am J Hum Genet, 2016)
Knowledge of the genetic basis of the type 2 diabetes (T2D)-related quantitative traits fasting glucose (FG) and insulin (FI) in African ancestry (AA) individuals has been limited. In non-diabetic subjects of AA (n = 20,209) and European ancestry (EA; n = 57,292), we performed trans-ethnic (AA+EA) fine-mapping of 54 established EA FG or FI loci with detailed functional annotation, assessed their relevance in AA individuals, and sought previously undescribed loci through trans-ethnic (AA+EA) meta-analysis. We narrowed credible sets of variants driving association signals for 22/54 EA-associated loci; 18/22 credible sets overlapped with active islet-specific enhancers or transcription factor (TF) binding sites, and 21/22 contained at least one TF motif. Of the 54 EA-associated loci, 23 were shared between EA and AA. Replication with an additional 10,096 AA individuals identified two previously undescribed FI loci, chrX FAM133A (rs213676) and chr5 PELO (rs6450057). Trans-ethnic analyses with regulatory annotation illuminate the genetic architecture of glycemic traits and suggest gene regulation as a target to advance precision medicine for T2D. Our approach to utilize state-of-the-art functional annotation and implement trans-ethnic association analysis for discovery and fine-mapping offers a framework for further follow-up and characterization of GWAS signals of complex trait loci.

Twenty-eight genetic loci associated with ST-T-wave amplitudes of the electrocardiogram. - Verweij, Niek; Mateo Leach, Irene; Isaacs, Aaron; Arking, Dan E; Bis, Joshua C; Pers, Tune H; van den Berg, Marten E; Lyytikäinen, Leo-Pekka; Barnett, Phil; Wang, Xinchen; Soliman, Elsayed Z; van Duijn, Cornelia M; et al. (Hum Mol Genet, 2016)
The ST-segment and adjacent T-wave (ST-T wave) amplitudes of the electrocardiogram are quantitative characteristics of cardiac repolarization. Repolarization abnormalities have been linked to ventricular arrhythmias and sudden cardiac death. We performed the first genome-wide association meta-analysis of ST-T-wave amplitudes in up to 37 977 individuals identifying 71 robust genotype-phenotype associations clustered within 28 independent loci. Fifty-four genes were prioritized as candidates underlying the phenotypes, including genes with established roles in the cardiac repolarization phase (SCN5A/SCN10A, KCND3, KCNB1, NOS1AP and HEY2) and others with as yet undefined cardiac function. These associations may provide insights in the spatiotemporal contribution of genetic variation influencing cardiac repolarization and provide novel leads for future functional follow-up.
Keywords: Adaptor Proteins, Signal Transducing; Arrhythmias, Cardiac; Basic Helix-Loop-Helix Transcription Factors; Brugada Syndrome; Cardiac Conduction System Disease; Death, Sudden, Cardiac; Electrocardiography; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Heart Conduction System; Humans; Male; NAV1.5 Voltage-Gated Sodium Channel; Polymorphism, Single Nucleotide; Repressor Proteins; Shab Potassium Channels; Shal Potassium Channels

Whole Exome Sequencing in Atrial Fibrillation. - Lubitz, Steven A; Brody, Jennifer A; Bihlmeyer, Nathan A; Roselli, Carolina; Weng, Lu-Chen; Christophersen, Ingrid E; Alonso, Alvaro; Boerwinkle, Eric; Gibbs, Richard A; Bis, Joshua C; Cupples, L Adrienne; Mohler, Peter J; et al. (PLoS Genet, 2016)
Atrial fibrillation (AF) is a morbid and heritable arrhythmia. Over 35 genes have been reported to underlie AF, most of which were described in small candidate gene association studies. Replication remains lacking for most, and therefore the contribution of coding variation to AF susceptibility remains poorly understood. We examined whole exome sequencing data in a large community-based sample of 1,734 individuals with and 9,423 without AF from the Framingham Heart Study, Cardiovascular Health Study, Atherosclerosis Risk in Communities Study, and NHLBI-GO Exome Sequencing Project and meta-analyzed the results. We also examined whether genetic variation was enriched in suspected AF genes (N = 37) in AF cases versus controls. The mean age ranged from 59 to 73 years; 8,656 (78%) were of European ancestry. None of the 99,404 common variants evaluated was significantly associated after adjusting for multiple testing. Among the most significantly associated variants was a common (allele frequency = 86%) missense variant in SYNPO2L (rs3812629, p.Pro707Leu, [odds ratio 1.27, 95% confidence interval 1.13-1.43, P = 6.6x10-5]) which lies at a known AF susceptibility locus and is in linkage disequilibrium with a top marker from prior analyses at the locus. We did not observe significant associations between rare variants and AF in gene-based tests. Individuals with AF did not display any statistically significant enrichment for common or rare coding variation in previously implicated AF genes. In conclusion, we did not observe associations between coding genetic variants and AF, suggesting that large-effect coding variation is not the predominant mechanism underlying AF. A coding variant in SYNPO2L requires further evaluation to determine whether it is causally related to AF. Efforts to identify biologically meaningful coding variation underlying AF may require large sample sizes or populations enriched for large genetic effects.

Whole-Exome Sequencing Identifies Loci Associated with Blood Cell Traits and Reveals a Role for Alternative GFI1B Splice Variants in Human Hematopoiesis. - Polfus, Linda M; Khajuria, Rajiv K; Schick, Ursula M; Pankratz, Nathan; Pazoki, Raha; Brody, Jennifer A; Chen, Ming-Huei; Auer, Paul L; Floyd, James S; Huang, Jie; Lange, Leslie; van Rooij, Frank J A; et al. (Am J Hum Genet, 2016)

740 adults from 20 prospective cohort studies - Wu, J. H. Y.; Marklund, M.; Imamura, F.; Tintle, N.; Ardisson Korat, A. V.; de Goede, J.; Zhou, X.; Yang, W. S.; de Oliveira Otto, M. C.; ger, J.; Qureshi, W.; Virtanen, J. K.; et al. (Lancet Diabetes Endocrinol, 2017)
The metabolic effects of omega-6 polyunsaturated fatty acids (PUFAs) remain contentious, and little evidence is available regarding their potential role in primary prevention of type 2 diabetes. We aimed to assess the associations of linoleic acid and arachidonic acid biomarkers with incident type 2 diabetes.\ We did a pooled analysis of new, harmonised, individual-level analyses for the biomarkers linoleic acid and its metabolite arachidonic acid and incident type 2 diabetes. We analysed data from 20 prospective cohort studies from ten countries (Iceland, the Netherlands, the USA, Taiwan, the UK, Germany, Finland, Australia, Sweden, and France), with biomarkers sampled between 1970 and 2010. Participants included in the analyses were aged 18 years or older and had data available for linoleic acid and arachidonic acid biomarkers at baseline. We excluded participants with type 2 diabetes at baseline. The main outcome was the association between omega-6 PUFA biomarkers and incident type 2 diabetes. We assessed the relative risk of type 2 diabetes prospectively for each cohort and lipid compartment separately using a prespecified analytic plan for exposures, covariates, effect modifiers, and analysis, and the findings were then pooled using inverse-variance weighted meta-analysis.\ 13).\ Findings suggest that linoleic acid has long-term benefits for the prevention of type 2 diabetes and that arachidonic acid is not harmful.\ Funders are shown in the appendix.

The Alzheimer's Disease Sequencing Project: Study design and sample selection. - Beecham, Gary W; Bis, J C; Martin, E R; Choi, S-H; DeStefano, A L; van Duijn, C M; Fornage, M; Gabriel, S B; Koboldt, D C; Larson, D E; Naj, A C; Psaty, B M; et al. (Neurol Genet, 2017)

Analysis commons, a team approach to discovery in a big-data environment for genetic epidemiology. - Brody, Jennifer A; Morrison, Alanna C; Bis, Joshua C; O'Connell, Jeffrey R; Brown, Michael R; Huffman, Jennifer E; Ames, Darren C; Carroll, Andrew; Conomos, Matthew P; Gabriel, Stacey; Gibbs, Richard A; Gogarten, Stephanie M; et al. (Nat Genet, 2017)

Association Between Telomere Length and Risk of Cancer and Non-Neoplastic Diseases: A Mendelian Randomization Study. - Haycock, Philip C; Burgess, Stephen; Nounu, Aayah; Zheng, Jie; Okoli, George N; Bowden, Jack; Wade, Kaitlin Hazel; Timpson, Nicholas J; Evans, David M; Willeit, Peter; Aviv, Abraham; Gaunt, Tom R; et al. (JAMA Oncol, 2017)
Importance: The causal direction and magnitude of the association between telomere length and incidence of cancer and non-neoplastic diseases is uncertain owing to the susceptibility of observational studies to confounding and reverse causation. Objective: To conduct a Mendelian randomization study, using germline genetic variants as instrumental variables, to appraise the causal relevance of telomere length for risk of cancer and non-neoplastic diseases. Data Sources: Genomewide association studies (GWAS) published up to January 15, 2015. Study Selection: GWAS of noncommunicable diseases that assayed germline genetic variation and did not select cohort or control participants on the basis of preexisting diseases. Of 163 GWAS of noncommunicable diseases identified, summary data from 103 were available. Data Extraction and Synthesis: Summary association statistics for single nucleotide polymorphisms (SNPs) that are strongly associated with telomere length in the general population. Main Outcomes and Measures: Odds ratios (ORs) and 95% confidence intervals (CIs) for disease per standard deviation (SD) higher telomere length due to germline genetic variation. Results: Summary data were available for 35 cancers and 48 non-neoplastic diseases, corresponding to 420 081 cases (median cases, 2526 per disease) and 1 093 105 controls (median, 6789 per disease). Increased telomere length due to germline genetic variation was generally associated with increased risk for site-specific cancers. The strongest associations (ORs [95% CIs] per 1-SD change in genetically increased telomere length) were observed for glioma, 5.27 (3.15-8.81); serous low-malignant-potential ovarian cancer, 4.35 (2.39-7.94); lung adenocarcinoma, 3.19 (2.40-4.22); neuroblastoma, 2.98 (1.92-4.62); bladder cancer, 2.19 (1.32-3.66); melanoma, 1.87 (1.55-2.26); testicular cancer, 1.76 (1.02-3.04); kidney cancer, 1.55 (1.08-2.23); and endometrial cancer, 1.31 (1.07-1.61). Associations were stronger for rarer cancers and at tissue sites with lower rates of stem cell division. There was generally little evidence of association between genetically increased telomere length and risk of psychiatric, autoimmune, inflammatory, diabetic, and other non-neoplastic diseases, except for coronary heart disease (OR, 0.78 [95% CI, 0.67-0.90]), abdominal aortic aneurysm (OR, 0.63 [95% CI, 0.49-0.81]), celiac disease (OR, 0.42 [95% CI, 0.28-0.61]) and interstitial lung disease (OR, 0.09 [95% CI, 0.05-0.15]). Conclusions and Relevance: It is likely that longer telomeres increase risk for several cancers but reduce risk for some non-neoplastic diseases, including cardiovascular diseases.
Keywords: Adult; Aged; Aged, 80 and over; Cardiovascular Diseases; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Germ-Line Mutation; Humans; Male; Mendelian Randomization Analysis; Middle Aged; Neoplasms; Polymorphism, Single Nucleotide; Risk Assessment; Telomere; Telomere Homeostasis

Association of Diabetic Macular Edema and Proliferative Diabetic Retinopathy With Cardiovascular Disease: A Systematic Review and Meta-analysis. - Xie, Jing; Ikram, M Kamran; Cotch, Mary Frances; Klein, Barbara; Varma, Rohit; Shaw, Jonathan E; Klein, Ronald; Mitchell, Paul; Lamoureux, Ecosse L; Wong, Tien Yin (JAMA Ophthalmol, 2017)
Importance: Previous studies on the relationship between diabetic retinopathy (DR) and cardiovascular disease (CVD) focused on the early stages of DR. Understanding whether patients with type 2 diabetes and severe stages of DR (diabetic macular edema [DME] and proliferative diabetic retinopathy [PDR]) have a higher risk of CVD will allow physicians to more effectively counsel patients. Objective: To examine the association of severe stages of DR (DME and PDR) with incident CVD in patients with type 2 diabetes. Data Sources: English-language publications were reviewed for articles evaluating the relationship of DR and CVD in MEDLINE, EMBASE, Current Contents, and the Cochrane Library from inception (January 1, 1950) to December 31, 2014, using the search terms diabetic retinopathy OR macular edema AND stroke OR cerebrovascular disease OR coronary artery disease OR heart failure OR myocardial infarction OR angina pectoris OR acute coronary syndrome OR coronary artery disease OR cardiomyopathy. Study Selection: Among 656 studies screened for eligibility, 7604 individuals were included from 8 prospective population-based studies with data on photographic-based DR grading, follow-up visits, and well-defined incident CVD end point. Data Extraction and Synthesis: Two independent reviewers conducted a systematic search of the 4 databases, and a single pooled database was developed. Incidence rate ratios (IRRs) were estimated for patients with DME, PDR, and vision-threatening DR, compared with persons without these conditions, by using individual participant data followed by a standard inverse-variance meta-analysis (2-step analysis). The review and analyses were performed from January 1, 2009, to January 1, 2017. Main Outcome and Measures: Incident CVD, including coronary heart disease, stroke, or death from cardiovascular causes. Results: Among 7604 patients with type 2 diabetes, the prevalence of DME was 4.6% and PDR, 7.4%. After a mean follow-up of 5.9 years (range, 3.2-10.1 years), 1203 incident CVD events, including 916 coronary heart disease cases, were reported. Persons with DME or PDR were more likely to have incident CVD (IRR, 1.39; 95% CI, 1.16-1.67) and fatal CVD (IRR, 2.33; 95% CI, 1.49-3.67) compared with those without DME or PDR. Conclusions and Relevance: Patients with type 2 diabetes and DME or PDR have an increased risk of incident CVD, which suggests that these persons should be followed up more closely to prevent CVD.
Keywords: Cardiovascular Diseases; Diabetic Retinopathy; Global Health; Humans; Incidence; Macular Edema; Risk Factors

Bivariate Genome-Wide Association Study of Depressive Symptoms with Type 2 Diabetes and Quantitative Glycemic Traits. - Haljas, Kadri; Amare, Azmeraw T; Alizadeh, Behrooz Z; Hsu, Yi-Hsiang; Mosley, Thomas; Newman, Anne; Murabito, Joanne; Tiemeier, Henning; Tanaka, Toshiko; van Duijn, Cornelia; Ding, Jingzhong; Llewellyn, David J; et al. (Psychosom Med, 2017)
OBJECTIVE: Shared genetic background may explain phenotypic associations between depression and Type-2-Diabetes (T2D). We aimed to study, on a genome-wide level, if genetic correlation and pleiotropic loci exist between depressive symptoms and T2D or glycemic traits. METHODS: We estimated SNP-based heritability and analyzed genetic correlation between depressive symptoms and T2D and glycemic traits with the LD Score Regression (LDSC) by combining summary statistics of previously conducted meta-analyses for depressive symptoms by CHARGE consortium (N = 51,258), T2D by Diagram consortium (N = 34,840 patients and 114,981 controls), fasting glucose, fasting insulin, HOMA-β, and HOMA-IR by MAGIC consortium (N = 58,074). Finally, we investigated pleiotropic loci using a bivariate GWAS approach with summary statistics from GWAS meta-analyses and reported loci with genome-wide significant bivariate association p-value (p < 5x10). Biological annotation and function of significant pleiotropic SNPs were assessed in several databases. RESULTS: The SNP-based heritability ranged from 0.04 to 0.10 in each individual trait. In the LDSC analyses, depressive symptoms showed no significant genetic correlation with T2D or glycemic traits (p > 0.37). Yet, we identified pleiotropic genetic variations for depressive symptoms and T2D (in the IGF2BP2, CDKAL1, CDKN2B-AS, and PLEKHA1 genes), and fasting glucose (in the MADD, CDKN2B-AS, PEX16, and MTNR1B genes). CONCLUSIONS: We found no significant overall genetic correlations between depressive symptoms, T2D or glycemic traits suggesting major differences in underlying biology of these traits. Yet, several potential pleiotropic loci were identified between depressive symptoms, T2D and fasting glucose suggesting that previously established phenotypic associations may be partly explained by genetic variation in these specific loci.

Comparison of HapMap and 1000 Genomes Reference Panels in a Large-Scale Genome-Wide Association Study. - de Vries, Paul S; Sabater-Lleal, Maria; Chasman, Daniel I; Trompet, Stella; Ahluwalia, Tarunveer S; Teumer, Alexander; Kleber, Marcus E; Chen, Ming-Huei; Wang, Jie Jin; Attia, John R; Marioni, Riccardo E; Steri, Maristella; et al. (PLoS One, 2017)
An increasing number of genome-wide association (GWA) studies are now using the higher resolution 1000 Genomes Project reference panel (1000G) for imputation, with the expectation that 1000G imputation will lead to the discovery of additional associated loci when compared to HapMap imputation. In order to assess the improvement of 1000G over HapMap imputation in identifying associated loci, we compared the results of GWA studies of circulating fibrinogen based on the two reference panels. Using both HapMap and 1000G imputation we performed a meta-analysis of 22 studies comprising the same 91,953 individuals. We identified six additional signals using 1000G imputation, while 29 loci were associated using both HapMap and 1000G imputation. One locus identified using HapMap imputation was not significant using 1000G imputation. The genome-wide significance threshold of 5×10-8 is based on the number of independent statistical tests using HapMap imputation, and 1000G imputation may lead to further independent tests that should be corrected for. When using a stricter Bonferroni correction for the 1000G GWA study (P-value < 2.5×10-8), the number of loci significant only using HapMap imputation increased to 4 while the number of loci significant only using 1000G decreased to 5. In conclusion, 1000G imputation enabled the identification of 20% more loci than HapMap imputation, although the advantage of 1000G imputation became less clear when a stricter Bonferroni correction was used. More generally, our results provide insights that are applicable to the implementation of other dense reference panels that are under development.

The complex genetics of gait speed: genome-wide meta-analysis approach. - Ben-Avraham, Dan; Karasik, David; Verghese, Joe; Lunetta, Kathryn L; Smith, Jennifer A; Eicher, John D; Vered, Rotem; Deelen, Joris; Arnold, Alice M; Buchman, Aron S; Tanaka, Toshiko; Faul, Jessica D; et al. (Aging (Albany NY), 2017)
Emerging evidence suggests that the basis for variation in late-life mobility is attributable, in part, to genetic factors, which may become increasingly important with age. Our objective was to systematically assess the contribution of genetic variation to gait speed in older individuals. We conducted a meta-analysis of gait speed GWASs in 31,478 older adults from 17 cohorts of the CHARGE consortium, and validated our results in 2,588 older adults from 4 independent studies. We followed our initial discoveries with network and eQTL analysis of candidate signals in tissues. The meta-analysis resulted in a list of 536 suggestive genome wide significant SNPs in or near 69 genes. Further interrogation with Pathway Analysis placed gait speed as a polygenic complex trait in five major networks. Subsequent eQTL analysis revealed several SNPs significantly associated with the expression of PRSS16, WDSUB1 and PTPRT, which in addition to the meta-analysis and pathway suggested that genetic effects on gait speed may occur through synaptic function and neuronal development pathways. No genome-wide significant signals for gait speed were identified from this moderately large sample of older adults, suggesting that more refined physical function phenotypes will be needed to identify the genetic basis of gait speed in aging.

Development of a Claims-based Frailty Indicator Anchored to a Well-established Frailty Phenotype. - Segal, Jodi B; Chang, Hsien-Yen; Du, Yu; D Walston, Jeremy; C Carlson, Michelle; Varadhan, Ravi (Med Care, 2017)
BACKGROUND: Fried and colleagues described a frailty phenotype measured in the Cardiovascular Health Study (CHS). This phenotype is manifest when ≥3 of the following are present: low grip strength, low energy, slowed waking speed, low physical activity, or unintentional weight loss. We sought to approximate frailty phenotype using only administrative claims data to enable frailty to be assessed without physical performance measures. STUDY DESIGN: We used the CHS cohort data linked to participants Medicare claims. The reference standard was the frailty phenotype measured at visits 5 and 9. With penalized logistic regression, we developed a parsimonious index for predicting the frailty phenotype using a linear combination of diagnoses, operationalized with claims data. We assessed the predictive validity of frailty index by examining how well it predicted common aging-related outcomes including hospitalization, disability, and death. RESULTS: There were 4454 CHS participants from 4 clinical sites. In total, 84% were white, 58% were women and their mean age was 72 years at enrollment. Approximately 11% of the cohort was frail. The model had an area under the receiver operating curve of 0.75 to concurrently predict a frailty phenotype. This Claims-based Frailty Indicator significantly predicted death (odds ratio, 1.84), time to death (hazards ratio, 1.71), number of hospital admissions (incidence rate ratio, 1.74), and nursing home admission (odds ratio, 1.47) in models adjusted for age and sex. CONCLUSIONS: Claims data alone can be used to classify individuals as frail and nonfrail. The Claims-based Frailty Indicator might be used in research with large datasets for confounding adjustment or risk prediction. The indicator might also be used for emergency preparedness for identification of regions enriched with frail individuals.This is an open-access article distributed under the terms of the Creative Commons Attribution-Non Commercial-No Derivatives License 4.0 (CCBY-NC-ND), where it is permissible to download and share the work provided it is properly cited. The work cannot be changed in any way or used commercially without permission from the journal. http://creativecommons.org/licenses/by-nc-nd/4.0/.

Discovery and fine-mapping of adiposity loci using high density imputation of genome-wide association studies in individuals of African ancestry: African ancestry anthropometry genetics consortium. - Ng, Maggie C Y; Graff, Mariaelisa; Lu, Yingchang; Justice, Anne E; Mudgal, Poorva; Liu, Ching-Ti; Young, Kristin; Yanek, Lisa R; Feitosa, Mary F; Wojczynski, Mary K; Rand, Kristin; Brody, Jennifer A; et al. (PLoS Genet, 2017)
Genome-wide association studies (GWAS) have identified >300 loci associated with measures of adiposity including body mass index (BMI) and waist-to-hip ratio (adjusted for BMI, WHRadjBMI), but few have been identified through screening of the African ancestry genomes. We performed large scale meta-analyses and replications in up to 52,895 individuals for BMI and up to 23,095 individuals for WHRadjBMI from the African Ancestry Anthropometry Genetics Consortium (AAAGC) using 1000 Genomes phase 1 imputed GWAS to improve coverage of both common and low frequency variants in the low linkage disequilibrium African ancestry genomes. In the sex-combined analyses, we identified one novel locus (TCF7L2/HABP2) for WHRadjBMI and eight previously established loci at P < 5×10-8: seven for BMI, and one for WHRadjBMI in African ancestry individuals. An additional novel locus (SPRYD7/DLEU2) was identified for WHRadjBMI when combined with European GWAS. In the sex-stratified analyses, we identified three novel loci for BMI (INTS10/LPL and MLC1 in men, IRX4/IRX2 in women) and four for WHRadjBMI (SSX2IP, CASC8, PDE3B and ZDHHC1/HSD11B2 in women) in individuals of African ancestry or both African and European ancestry. For four of the novel variants, the minor allele frequency was low (<5%). In the trans-ethnic fine mapping of 47 BMI loci and 27 WHRadjBMI loci that were locus-wide significant (P < 0.05 adjusted for effective number of variants per locus) from the African ancestry sex-combined and sex-stratified analyses, 26 BMI loci and 17 WHRadjBMI loci contained ≤ 20 variants in the credible sets that jointly account for 99% posterior probability of driving the associations. The lead variants in 13 of these loci had a high probability of being causal. As compared to our previous HapMap imputed GWAS for BMI and WHRadjBMI including up to 71,412 and 27,350 African ancestry individuals, respectively, our results suggest that 1000 Genomes imputation showed modest improvement in identifying GWAS loci including low frequency variants. Trans-ethnic meta-analyses further improved fine mapping of putative causal variants in loci shared between the African and European ancestry populations.

Discovery and replication of SNP-SNP interactions for quantitative lipid traits in over 60,000 individuals. - Holzinger, Emily R; Verma, Shefali S; Moore, Carrie B; Hall, Molly; De, Rishika; Gilbert-Diamond, Diane; Lanktree, Matthew B; Pankratz, Nathan; Amuzu, Antoinette; Burt, Amber; Dale, Caroline; Dudek, Scott; et al. (BioData Min, 2017)
BACKGROUND: The genetic etiology of human lipid quantitative traits is not fully elucidated, and interactions between variants may play a role. We performed a gene-centric interaction study for four different lipid traits: low-density lipoprotein cholesterol (LDL-C), high-density lipoprotein cholesterol (HDL-C), total cholesterol (TC), and triglycerides (TG). RESULTS: Our analysis consisted of a discovery phase using a merged dataset of five different cohorts (n = 12,853 to n = 16,849 depending on lipid phenotype) and a replication phase with ten independent cohorts totaling up to 36,938 additional samples. Filters are often applied before interaction testing to correct for the burden of testing all pairwise interactions. We used two different filters: 1. A filter that tested only single nucleotide polymorphisms (SNPs) with a main effect of p < 0.001 in a previous association study. 2. A filter that only tested interactions identified by Biofilter 2.0. Pairwise models that reached an interaction significance level of p < 0.001 in the discovery dataset were tested for replication. We identified thirteen SNP-SNP models that were significant in more than one replication cohort after accounting for multiple testing. CONCLUSIONS: These results may reveal novel insights into the genetic etiology of lipid levels. Furthermore, we developed a pipeline to perform a computationally efficient interaction analysis with multi-cohort replication.

Discovery of novel heart rate-associated loci using the Exome Chip. - van den Berg, Marten E; Warren, Helen R; Cabrera, Claudia P; Verweij, Niek; Mifsud, Borbala; Haessler, Jeffrey; Bihlmeyer, Nathan A; Fu, Yi-Ping; Weiss, Stefan; Lin, Henry J; Grarup, Niels; Li-Gao, Ruifang; et al. (Hum Mol Genet, 2017)
Background Resting heart rate is a heritable trait, and an increase in heart rate is associated with increased mortality risk. GWAS analyses have found loci associated with resting heart rate, at the time of our study these loci explained 0.9% of the variation.Aim To discover new genetic loci associated with heart rate from Exome Chip meta-analyses.Methods Heart rate was measured from either elecrtrocardiograms or pulse recordings. We meta-analysed heart rate association results from 104,452 European-ancestry individuals from 30 cohorts, genotyped using the Exome Chip. Twenty-four variants were selected for follow-up in an independent dataset (UK Biobank, N = 134,251). Conditional and gene-based testing was undertaken, and variants were investigated with bioinformatics methods.Results We discovered five novel heart rate loci, and one new independent low-frequency non-synonymous variant in an established heart rate locus (KIAA1755). Lead variants in four of the novel loci are non-synonymous variants in the genes C10orf71, DALDR3, TESK2, SEC31B. The variant at SEC31B is significantly associated with SEC31B expression in heart and tibial nerve tissue. Further candidate genes were detected from long range regulatory chromatin interactions in heart tissue (SCD, SLF2, MAPK8). We observed significant enrichment in DNase I hypersensitive sites in fetal heart and lung. Moreover, enrichment was seen for the first time in human neuronal progenitor cells (derived from embryonic stem cells) and fetal muscle samples by including our novel variants.Conclusion Our findings advance the knowledge of the genetic architecture of heart rate, and indicate new candidate genes for follow-up functional studies.

DNA Methylation Analysis Identifies Loci for Blood Pressure Regulation. - Richard, Melissa A; Huan, Tianxiao; Ligthart, Symen; Gondalia, Rahul; Jhun, Min A; Brody, Jennifer A; Irvin, Marguerite R; Marioni, Riccardo; Shen, Jincheng; Tsai, Pei-Chien; Montasser, May E; Jia, Yucheng; et al. (Am J Hum Genet, 2017)
Genome-wide association studies have identified hundreds of genetic variants associated with blood pressure (BP), but sequence variation accounts for a small fraction of the phenotypic variance. Epigenetic changes may alter the expression of genes involved in BP regulation and explain part of the missing heritability. We therefore conducted a two-stage meta-analysis of the cross-sectional associations of systolic and diastolic BP with blood-derived genome-wide DNA methylation measured on the Infinium HumanMethylation450 BeadChip in 17,010 individuals of European, African American, and Hispanic ancestry. Of 31 discovery-stage cytosine-phosphate-guanine (CpG) dinucleotides, 13 replicated after Bonferroni correction (discovery: N = 9,828, p < 1.0 × 10-7; replication: N = 7,182, p < 1.6 × 10-3). The replicated methylation sites are heritable (h2 > 30%) and independent of known BP genetic variants, explaining an additional 1.4% and 2.0% of the interindividual variation in systolic and diastolic BP, respectively. Bidirectional Mendelian randomization among up to 4,513 individuals of European ancestry from 4 cohorts suggested that methylation at cg08035323 (TAF1B-YWHAQ) influences BP, while BP influences methylation at cg00533891 (ZMIZ1), cg00574958 (CPT1A), and cg02711608 (SLC1A5). Gene expression analyses further identified six genes (TSPAN2, SLC7A11, UNC93B1, CPT1A, PTMS, and LPCAT3) with evidence of triangular associations between methylation, gene expression, and BP. Additional integrative Mendelian randomization analyses of gene expression and DNA methylation suggested that the expression of TSPAN2 is a putative mediator of association between DNA methylation at cg23999170 and BP. These findings suggest that heritable DNA methylation plays a role in regulating BP independently of previously known genetic variants.
Keywords: Aged; Blood Pressure; CpG Islands; Cross-Sectional Studies; DNA Methylation; Epigenesis, Genetic; Genetic Variation; Genome-Wide Association Study; Humans; Mendelian Randomization Analysis; Middle Aged; Nerve Tissue Proteins; Quantitative Trait Loci; Tetraspanins

Exome-wide association study of plasma lipids in >300,000 individuals. - Liu, Dajiang J; Peloso, Gina M; Yu, Haojie; Butterworth, Adam S; Wang, Xiao; Mahajan, Anubha; Saleheen, Danish; Emdin, Connor; Alam, Dewan; Alves, Alexessander Couto; Amouyel, Philippe; Di Angelantonio, Emanuele; et al. (Nat Genet, 2017)
We screened variants on an exome-focused genotyping array in >300,000 participants (replication in >280,000 participants) and identified 444 independent variants in 250 loci significantly associated with total cholesterol (TC), high-density-lipoprotein cholesterol (HDL-C), low-density-lipoprotein cholesterol (LDL-C), and/or triglycerides (TG). At two loci (JAK2 and A1CF), experimental analysis in mice showed lipid changes consistent with the human data. We also found that: (i) beta-thalassemia trait carriers displayed lower TC and were protected from coronary artery disease (CAD); (ii) excluding the CETP locus, there was not a predictable relationship between plasma HDL-C and risk for age-related macular degeneration; (iii) only some mechanisms of lowering LDL-C appeared to increase risk for type 2 diabetes (T2D); and (iv) TG-lowering alleles involved in hepatic production of TG-rich lipoproteins (TM6SF2 and PNPLA3) tracked with higher liver fat, higher risk for T2D, and lower risk for CAD, whereas TG-lowering alleles involved in peripheral lipolysis (LPL and ANGPTL4) had no effect on liver fat but decreased risks for both T2D and CAD.
Keywords: Coronary Artery Disease; Diabetes Mellitus, Type 2; Exome; Genetic Association Studies; Genetic Predisposition to Disease; Genetic Variation; Genotype; Humans; Lipids; Macular Degeneration; Phenotype; Risk Factors

Factors Associated With Ischemic Stroke Survival and Recovery in Older Adults. - Winovich, Divya Thekkethala; Longstreth, William T; Arnold, Alice M; Varadhan, Ravi; Zeki Al Hazzouri, Adina; Cushman, Mary; Newman, Anne B; Odden, Michelle C (Stroke, 2017)
BACKGROUND AND PURPOSE: Little is known about factors that predispose older adults to poor recovery after a stroke. In this study, we sought to evaluate prestroke measures of frailty and related factors as markers of vulnerability to poor outcomes after ischemic stroke. METHODS: In participants aged 65 to 99 years with incident ischemic strokes from the Cardiovascular Health Study, we evaluated the association of several risk factors (frailty, frailty components, C-reactive protein, interleukin-6, and cystatin C) assessed before stroke with stroke outcomes of survival, cognitive decline (≥5 points on Modified Mini-Mental State Examination), and activities of daily living decline (increase in limitations). RESULTS: Among 717 participants with incident ischemic stroke with survival data, slow walking speed, low grip strength, and cystatin C were independently associated with shorter survival. Among participants <80 years of age, frailty and interleukin-6 were also associated with shorter survival. Among 509 participants with recovery data, slow walking speed, and low grip strength were associated with both cognitive and activities of daily living decline poststroke. C-reactive protein and interleukin-6 were associated with poststroke cognitive decline among men only. Frailty status was associated with activities of daily living decline among women only. CONCLUSIONS: Markers of physical function-walking speed and grip strength-were consistently associated with survival and recovery after ischemic stroke. Inflammation, kidney function, and frailty also seemed to be determinants of survival and recovery after an ischemic stroke. These markers of vulnerability may identify targets for differing pre and poststroke medical management and rehabilitation among older adults at risk of poor stroke outcomes.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Brain Ischemia; Cohort Studies; Female; Follow-Up Studies; Frail Elderly; Humans; Male; Recovery of Function; Risk Factors; Stroke; Survival Rate

Fifteen Genetic Loci Associated With the Electrocardiographic P Wave. - Christophersen, Ingrid E; Magnani, Jared W; Yin, Xiaoyan; Barnard, John; Weng, Lu-Chen; Arking, Dan E; Niemeijer, Maartje N; Lubitz, Steven A; Avery, Christy L; Duan, Qing; Felix, Stephan B; Bis, Joshua C; et al. (Circ Cardiovasc Genet, 2017)
BACKGROUND: The P wave on an ECG is a measure of atrial electric function, and its characteristics may serve as predictors for atrial arrhythmias. Increased mean P-wave duration and P-wave terminal force traditionally have been used as markers for left atrial enlargement, and both have been associated with increased risk of atrial fibrillation. Here, we explore the genetic basis of P-wave morphology through meta-analysis of genome-wide association study results for P-wave duration and P-wave terminal force from 12 cohort studies. METHODS AND RESULTS: We included 44 456 individuals, of which 6778 (16%) were of African ancestry. Genotyping, imputation, and genome-wide association study were performed at each study site. Summary-level results were meta-analyzed centrally using inverse-variance weighting. In meta-analyses of P-wave duration, we identified 6 significant (P<5×10-8) novel loci and replicated a prior association with SCN10A. We identified 3 loci at SCN5A, TBX5, and CAV1/CAV2 that were jointly associated with the PR interval, PR segment, and P-wave duration. We identified 6 novel loci in meta-analysis of P-wave terminal force. Four of the identified genetic loci were significantly associated with gene expression in 329 left atrial samples. Finally, we observed that some of the loci associated with the P wave were linked to overall atrial conduction, whereas others identified distinct phases of atrial conduction. CONCLUSIONS: We have identified 6 novel genetic loci associated with P-wave duration and 6 novel loci associated with P-wave terminal force. Future studies of these loci may aid in identifying new targets for drugs that may modify atrial conduction or treat atrial arrhythmias.
Keywords: Arrhythmias, Cardiac; Caveolin 1; Caveolin 2; Electrocardiography; Genetic Loci; Genome-Wide Association Study; Genotype; Heart Atria; Humans; NAV1.5 Voltage-Gated Sodium Channel; NAV1.8 Voltage-Gated Sodium Channel; T-Box Domain Proteins

Fine mapping of QT interval regions in global populations refines previously identified QT interval loci and identifies signals unique to African and Hispanic descent populations. - Avery, Christy L; Wassel, Christina L; Richard, Melissa A; Highland, Heather M; Bien, Stephanie; Zubair, Niha; Soliman, Elsayed Z; Fornage, Myriam; Bielinski, Suzette J; Tao, Ran; Seyerle, Amanda A; Shah, Sanjiv J; et al. (Heart Rhythm, 2017)
BACKGROUND: The electrocardiographically measured QT interval (QT) is heritable and its prolongation is an established risk factor for several cardiovascular diseases. Yet, most QT genetic studies have been performed in European ancestral populations, possibly reducing their global relevance. OBJECTIVE: To leverage diversity and improve biological insight, we fine mapped 16 of the 35 previously identified QT loci (46%) in populations of African American (n = 12,410) and Hispanic/Latino (n = 14,837) ancestry. METHODS: Racial/ethnic-specific multiple linear regression analyses adjusted for heart rate and clinical covariates were examined separately and in combination after inverse-variance weighted trans-ethnic meta-analysis. RESULTS: The 16 fine-mapped QT loci included on the Illumina Metabochip represented 21 independent signals, of which 16 (76%) were significantly (P-value≤9.1×10(-5)) associated with QT. Through sequential conditional analysis we also identified three trans-ethnic novel SNPs at ATP1B1, SCN5A-SCN10A, and KCNQ1 and three Hispanic/Latino-specific novel SNPs at NOS1AP and SCN5A-SCN10A (two novel SNPs) with evidence of associations with QT independent of previous identified GWAS lead SNPs. Linkage disequilibrium patterns helped to narrow the region likely to contain the functional variants at several loci, including NOS1AP, USP50-TRPM7, and PRKCA, although intervals surrounding SLC35F1-PLN and CNOT1 remained broad in size (>100 kb). Finally, bioinformatics-based functional characterization suggested a regulatory function in cardiac tissues for the majority of independent signals that generalized and the novel SNPs. CONCLUSION: Our findings suggest that a majority of identified SNPs implicate gene regulatory dysfunction in QT prolongation, that the same loci influence variation in QT across global populations, and that additional, novel, population-specific QT signals exist.

Generalization and fine mapping of European ancestry-based central adiposity variants in African ancestry populations. - Yoneyama, S; Yao, J; Guo, X; Fernandez-Rhodes, L; Lim, U; Boston, J; Bůžková, P; Carlson, C S; Cheng, I; Cochran, B; Cooper, R; Ehret, G; et al. (Int J Obes (Lond), 2017)
BACKGROUND/OBJECTIVES: Central adiposity measures such as waist circumference (WC) and waist-to-hip ratio (WHR) are associated with cardiometabolic disorders independently of body mass index (BMI) and are gaining clinically utility. Several studies report genetic variants associated with central adiposity, but most utilize only European ancestry populations. Understanding whether the genetic associations discovered among mainly European descendants are shared with African ancestry populations will help elucidate the biological underpinnings of abdominal fat deposition. SUBJECTS/METHODS: To identify the underlying functional genetic determinants of body fat distribution, we conducted an array-wide association meta-analysis among persons of African ancestry across seven studies/consortia participating in the Population Architecture using Genomics and Epidemiology (PAGE) consortium. We used the Metabochip array, designed for fine-mapping cardiovascular-associated loci, to explore novel array-wide associations with WC and WHR among 15 945 African descendants using all and sex-stratified groups. We further interrogated 17 known WHR regions for African ancestry-specific variants. RESULTS: Of the 17 WHR loci, eight single-nucleotide polymorphisms (SNPs) located in four loci were replicated in the sex-combined or sex-stratified meta-analyses. Two of these eight independently associated with WHR after conditioning on the known variant in European descendants (rs12096179 in TBX15-WARS2 and rs2059092 in ADAMTS9). In the fine-mapping assessment, the putative functional region was reduced across all four loci but to varying degrees (average 40% drop in number of putative SNPs and 20% drop in genomic region). Similar to previous studies, the significant SNPs in the female-stratified analysis were stronger than the significant SNPs from the sex-combined analysis. No novel associations were detected in the array-wide analyses. CONCLUSIONS: Of 17 previously identified loci, four loci replicated in the African ancestry populations of this study. Utilizing different linkage disequilibrium patterns observed between European and African ancestries, we narrowed the suggestive region containing causative variants for all four loci.

Genetic Interactions with Age, Sex, Body Mass Index, and Hypertension in Relation to Atrial Fibrillation: The AFGen Consortium. - Weng, Lu-Chen; Lunetta, Kathryn L; Müller-Nurasyid, Martina; Smith, Albert Vernon; Thériault, Sébastien; Weeke, Peter E; Barnard, John; Bis, Joshua C; Lyytikäinen, Leo-Pekka; Kleber, Marcus E; Martinsson, Andreas; Lin, Henry J; et al. (Sci Rep, 2017)
It is unclear whether genetic markers interact with risk factors to influence atrial fibrillation (AF) risk. We performed genome-wide interaction analyses between genetic variants and age, sex, hypertension, and body mass index in the AFGen Consortium. Study-specific results were combined using meta-analysis (88,383 individuals of European descent, including 7,292 with AF). Variants with nominal interaction associations in the discovery analysis were tested for association in four independent studies (131,441 individuals, including 5,722 with AF). In the discovery analysis, the AF risk associated with the minor rs6817105 allele (at the PITX2 locus) was greater among subjects ≤ 65 years of age than among those > 65 years (interaction p-value = 4.0 × 10-5). The interaction p-value exceeded genome-wide significance in combined discovery and replication analyses (interaction p-value = 1.7 × 10-8). We observed one genome-wide significant interaction with body mass index and several suggestive interactions with age, sex, and body mass index in the discovery analysis. However, none was replicated in the independent sample. Our findings suggest that the pathogenesis of AF may differ according to age in individuals of European descent, but we did not observe evidence of statistically significant genetic interactions with sex, body mass index, or hypertension on AF risk.

Genetic loci associated with chronic obstructive pulmonary disease overlap with loci for lung function and pulmonary fibrosis. - Hobbs, Brian D; de Jong, Kim; Lamontagne, Maxime; Bossé, Yohan; Shrine, Nick; Artigas, Maria Soler; Wain, Louise V; Hall, Ian P; Jackson, Victoria E; Wyss, Annah B; London, Stephanie J; North, Kari E; et al. (Nat Genet, 2017)
Chronic obstructive pulmonary disease (COPD) is a leading cause of mortality worldwide. We performed a genetic association study in 15,256 cases and 47,936 controls, with replication of select top results (P < 5 × 10(-6)) in 9,498 cases and 9,748 controls. In the combined meta-analysis, we identified 22 loci associated at genome-wide significance, including 13 new associations with COPD. Nine of these 13 loci have been associated with lung function in general population samples, while 4 (EEFSEC, DSP, MTCL1, and SFTPD) are new. We noted two loci shared with pulmonary fibrosis (FAM13A and DSP) but that had opposite risk alleles for COPD. None of our loci overlapped with genome-wide associations for asthma, although one locus has been implicated in joint susceptibility to asthma and obesity. We also identified genetic correlation between COPD and asthma. Our findings highlight new loci associated with COPD, demonstrate the importance of specific loci associated with lung function to COPD, and identify potential regions of genetic overlap between COPD and other respiratory diseases.

Genetic loci associated with heart rate variability and their effects on cardiac disease risk. - Nolte, Ilja M; Munoz, M Loretto; Tragante, Vinicius; Amare, Azmeraw T; Jansen, Rick; Vaez, Ahmad; von der Heyde, Benedikt; Avery, Christy L; Bis, Joshua C; Dierckx, Bram; van Dongen, Jenny; Gogarten, Stephanie M; et al. (Nat Commun, 2017)
Reduced cardiac vagal control reflected in low heart rate variability (HRV) is associated with greater risks for cardiac morbidity and mortality. In two-stage meta-analyses of genome-wide association studies for three HRV traits in up to 53,174 individuals of European ancestry, we detect 17 genome-wide significant SNPs in eight loci. HRV SNPs tag non-synonymous SNPs (in NDUFA11 and KIAA1755), expression quantitative trait loci (eQTLs) (influencing GNG11, RGS6 and NEO1), or are located in genes preferentially expressed in the sinoatrial node (GNG11, RGS6 and HCN4). Genetic risk scores account for 0.9 to 2.6% of the HRV variance. Significant genetic correlation is found for HRV with heart rate (-0.74<rg<-0.55) and blood pressure (-0.35<rg<-0.20). These findings provide clinically relevant biological insight into heritable variation in vagal heart rhythm regulation, with a key role for genetic variants (GNG11, RGS6) that influence G-protein heterotrimer action in GIRK-channel induced pacemaker membrane hyperpolarization.

{Genetic Risk Prediction of Atrial Fibrillation - Lubitz, S. A.; Yin, X.; Lin, H. J.; Kolek, M.; Smith, J. G.; Trompet, S.; Rienstra, M.; Rost, N. S.; Teixeira, P. L.; Almgren, P.; Anderson, C. D.; Chen, L. Y.; et al. (Circulation, 2017)
Atrial fibrillation (AF) has a substantial genetic basis. Identification of individuals at greatest AF risk could minimize the incidence of cardioembolic stroke.\ To determine whether genetic data can stratify risk for development of AF, we examined associations between AF genetic risk scores and incident AF in 5 prospective studies comprising 18 919 individuals of European ancestry. We examined associations between AF genetic risk scores and ischemic stroke in a separate study of 509 ischemic stroke cases (202 cardioembolic [40%]) and 3028 referents. Scores were based on 11 to 719 common variants (≥5%) associated with AF at P values ranging from <1×10-3 to <1×10-8 in a prior independent genetic association study.\ Incident AF occurred in 1032 individuals (5.5%). AF genetic risk scores were associated with new-onset AF after adjustment for clinical risk factors. The pooled hazard ratio for incident AF for the highest versus lowest quartile of genetic risk scores ranged from 1.28 (719 variants; 95% confidence interval, 1.13-1.46; P=1.5×10-4) to 1.67 (25 variants; 95% confidence interval, 1.47-1.90; P=9.3×10-15). Discrimination of combined clinical and genetic risk scores varied across studies and scores (maximum C statistic, 0.629-0.811; maximum ΔC statistic from clinical score alone, 0.009-0.017). AF genetic risk was associated with stroke in age- and sex-adjusted models. For example, individuals in the highest versus lowest quartile of a 127-variant score had a 2.49-fold increased odds of cardioembolic stroke (95% confidence interval, 1.39-4.58; P=2.7×10-3). The effect persisted after the exclusion of individuals (n=70) with known AF (odds ratio, 2.25; 95% confidence interval, 1.20-4.40; P=0.01).\ Comprehensive AF genetic risk scores were associated with incident AF beyond associations for clinical AF risk factors but offered small improvements in discrimination. AF genetic risk was also associated with cardioembolic stroke in age- and sex-adjusted analyses. Efforts are warranted to determine whether AF genetic risk may improve identification of subclinical AF or help distinguish between stroke mechanisms.

Genetically Determined Plasma Lipid Levels and Risk of Diabetic Retinopathy: A Mendelian Randomization Study. - Sobrin, Lucia; Chong, Yong He; Fan, Qiao; Gan, Alfred; Stanwyck, Lynn K; Kaidonis, Georgia; Craig, Jamie E; Kim, Jihye; Liao, Wen-Ling; Huang, Yu-Chuen; Lee, Wen-Jane; Hung, Yi-Jen; et al. (Diabetes, 2017)
Results from observational studies examining dyslipidemia as a risk factor for diabetic retinopathy (DR) have been inconsistent. We evaluated the causal relationship between plasma lipids and DR using a Mendelian randomization approach. We pooled genome-wide association studies summary statistics from 18 studies for two DR phenotypes: any DR (N = 2,969 case and 4,096 control subjects) and severe DR (N = 1,277 case and 3,980 control subjects). Previously identified lipid-associated single nucleotide polymorphisms served as instrumental variables. Meta-analysis to combine the Mendelian randomization estimates from different cohorts was conducted. There was no statistically significant change in odds ratios of having any DR or severe DR for any of the lipid fractions in the primary analysis that used single nucleotide polymorphisms that did not have a pleiotropic effect on another lipid fraction. Similarly, there was no significant association in the Caucasian and Chinese subgroup analyses. This study did not show evidence of a causal role of the four lipid fractions on DR. However, the study had limited power to detect odds ratios less than 1.23 per SD in genetically induced increase in plasma lipid levels, thus we cannot exclude that causal relationships with more modest effect sizes exist.
Keywords: Aged; Diabetic Retinopathy; Female; Genome-Wide Association Study; Humans; Lipids; Male; Mendelian Randomization Analysis; Middle Aged; Polymorphism, Single Nucleotide; Risk

{Genome-wide association analysis identifies novel blood pressure loci and offers biological insights into cardiovascular risk - Warren, H. R.; Evangelou, E.; Cabrera, C. P.; Gao, H.; Ren, M.; Mifsud, B.; Ntalla, I.; Surendran, P.; Liu, C.; Cook, J. P.; Kraja, A. T.; Drenos, F.; et al. (Nat Genet, 2017)
Elevated blood pressure is the leading heritable risk factor for cardiovascular disease worldwide. We report genetic association of blood pressure (systolic, diastolic, pulse pressure) among UK Biobank participants of European ancestry with independent replication in other cohorts, and robust validation of 107 independent loci. We also identify new independent variants at 11 previously reported blood pressure loci. In combination with results from a range of in silico functional analyses and wet bench experiments, our findings highlight new biological pathways for blood pressure regulation enriched for genes expressed in vascular tissues and identify potential therapeutic targets for hypertension. Results from genetic risk score models raise the possibility of a precision medicine approach through early lifestyle intervention to offset the impact of blood pressure-raising genetic variants on future cardiovascular disease risk.

Genome-wide association meta-analysis of fish and EPA+DHA consumption in 17 US and European cohorts. - Mozaffarian, Dariush; Dashti, Hassan S; Wojczynski, Mary K; Chu, Audrey Y; Nettleton, Jennifer A; Männistö, Satu; Kristiansson, Kati; Reedik, Mägi; Lahti, Jari; Houston, Denise K; Cornelis, Marilyn C; van Rooij, Frank J A; et al. (PLoS One, 2017)
BACKGROUND: Regular fish and omega-3 consumption may have several health benefits and are recommended by major dietary guidelines. Yet, their intakes remain remarkably variable both within and across populations, which could partly owe to genetic influences. OBJECTIVE: To identify common genetic variants that influence fish and dietary eicosapentaenoic acid plus docosahexaenoic acid (EPA+DHA) consumption. DESIGN: We conducted genome-wide association (GWA) meta-analysis of fish (n = 86,467) and EPA+DHA (n = 62,265) consumption in 17 cohorts of European descent from the CHARGE (Cohorts for Heart and Aging Research in Genomic Epidemiology) Consortium Nutrition Working Group. Results from cohort-specific GWA analyses (additive model) for fish and EPA+DHA consumption were adjusted for age, sex, energy intake, and population stratification, and meta-analyzed separately using fixed-effect meta-analysis with inverse variance weights (METAL software). Additionally, heritability was estimated in 2 cohorts. RESULTS: Heritability estimates for fish and EPA+DHA consumption ranged from 0.13-0.24 and 0.12-0.22, respectively. A significant GWA for fish intake was observed for rs9502823 on chromosome 6: each copy of the minor allele (FreqA = 0.015) was associated with 0.029 servings/day (~1 serving/month) lower fish consumption (P = 1.96x10-8). No significant association was observed for EPA+DHA, although rs7206790 in the obesity-associated FTO gene was among top hits (P = 8.18x10-7). Post-hoc calculations demonstrated 95% statistical power to detect a genetic variant associated with effect size of 0.05% for fish and 0.08% for EPA+DHA. CONCLUSIONS: These novel findings suggest that non-genetic personal and environmental factors are principal determinants of the remarkable variation in fish consumption, representing modifiable targets for increasing intakes among all individuals. Genes underlying the signal at rs72838923 and mechanisms for the association warrant further investigation.
Keywords: Adult; Aged; Cohort Studies; Docosahexaenoic Acids; Eicosapentaenoic Acid; Europe; European Continental Ancestry Group; Female; Genome-Wide Association Study; Humans; Male; Middle Aged; Seafood; United States

Genome-Wide Association Study Meta-Analysis of Long-Term Average Blood Pressure in East Asians. - Li, Changwei; Kim, Yun Kyoung; Dorajoo, Rajkumar; Li, Huaixing; Lee, I-Te; Cheng, Ching-Yu; He, Meian; Sheu, Wayne H-H; Guo, Xiuqing; Ganesh, Santhi K; He, Jiang; Lee, Juyoung; et al. (Circ Cardiovasc Genet, 2017)
BACKGROUND: Genome-wide single marker and gene-based meta-analyses of long-term average (LTA) blood pressure (BP) phenotypes may reveal novel findings for BP. METHODS AND RESULTS: We conducted genome-wide analysis among 18 422 East Asian participants (stage 1) followed by replication study of ≤46 629 participants of European ancestry (stage 2). Significant single-nucleotide polymorphisms and genes were determined by a P<5.0×10-8 and 2.5×10-6, respectively, in joint analyses of stage-1 and stage-2 data. We identified 1 novel ARL3 variant, rs4919669 at 10q24.32, influencing LTA systolic BP (stage-1 P=5.03×10-8, stage-2 P=8.64×10-3, joint P=2.63×10-8) and mean arterial pressure (stage-1 P=3.59×10-9, stage-2 P=2.35×10-2, joint P=2.64×10-8). Three previously reported BP loci (WBP1L, NT5C2, and ATP2B1) were also identified for all BP phenotypes. Gene-based analysis provided the first robust evidence for association of KCNJ11 with LTA systolic BP (stage-1 P=8.55×10-6, stage-2 P=1.62×10-5, joint P=3.28×10-9) and mean arterial pressure (stage-1 P=9.19×10-7, stage-2 P=9.69×10-5, joint P=2.15×10-9) phenotypes. Fourteen genes (TMEM180, ACTR1A, SUFU, ARL3, SFXN2, WBP1L, CYP17A1, C10orf32, C10orf32-ASMT, AS3MT, CNNM2, and NT5C2 at 10q24.32; ATP2B1 at 12q21.33; and NCR3LG1 at 11p15.1) implicated by previous genome-wide association study meta-analyses were also identified. Among the loci identified by the previous genome-wide association study meta-analysis of LTA BP, we transethnically replicated associations of the KCNK3 marker rs1275988 at 2p23.3 with LTA systolic BP and mean arterial pressure phenotypes (P=1.27×10-4 and 3.30×10-4, respectively). CONCLUSIONS: We identified 1 novel variant and 1 novel gene and present the first direct evidence of relevance of the KCNK3 locus for LTA BP among East Asians.
Keywords: Asian Continental Ancestry Group; Blood Pressure; Far East; Female; Genetic Loci; Genome-Wide Association Study; Humans; Male; Phenotype; Polymorphism, Single Nucleotide

A genome-wide interaction analysis of tricyclic/tetracyclic antidepressants and RR and QT intervals: a pharmacogenomics study from the Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) consortium. - Noordam, Raymond; Sitlani, Colleen M; Avery, Christy L; Stewart, James D; Gogarten, Stephanie M; Wiggins, Kerri L; Trompet, Stella; Warren, Helen R; Sun, Fangui; Evans, Daniel S; Li, Xiaohui; Li, Jin; et al. (J Med Genet, 2017)
BACKGROUND: Increased heart rate and a prolonged QT interval are important risk factors for cardiovascular morbidity and mortality, and can be influenced by the use of various medications, including tricyclic/tetracyclic antidepressants (TCAs). We aim to identify genetic loci that modify the association between TCA use and RR and QT intervals. METHODS AND RESULTS: We conducted race/ethnic-specific genome-wide interaction analyses (with HapMap phase II imputed reference panel imputation) of TCAs and resting RR and QT intervals in cohorts of European (n=45 706; n=1417 TCA users), African (n=10 235; n=296 TCA users) and Hispanic/Latino (n=13 808; n=147 TCA users) ancestry, adjusted for clinical covariates. Among the populations of European ancestry, two genome-wide significant loci were identified for RR interval: rs6737205 in BRE (β=56.3, pinteraction=3.9e(-9)) and rs9830388 in UBE2E2 (β=25.2, pinteraction=1.7e(-8)). In Hispanic/Latino cohorts, rs2291477 in TGFBR3 significantly modified the association between TCAs and QT intervals (β=9.3, pinteraction=2.55e(-8)). In the meta-analyses of the other ethnicities, these loci either were excluded from the meta-analyses (as part of quality control), or their effects did not reach the level of nominal statistical significance (pinteraction>0.05). No new variants were identified in these ethnicities. No additional loci were identified after inverse-variance-weighted meta-analysis of the three ancestries. CONCLUSIONS: Among Europeans, TCA interactions with variants in BRE and UBE2E2 were identified in relation to RR intervals. Among Hispanic/Latinos, variants in TGFBR3 modified the relation between TCAs and QT intervals. Future studies are required to confirm our results.

Genome-Wide Interactions with Dairy Intake for Body Mass Index in Adults of European Descent. - Smith, Caren E; Follis, Jack L; Dashti, Hassan S; Tanaka, Toshiko; Graff, Mariaelisa; Fretts, Amanda M; Kilpeläinen, Tuomas O; Wojczynski, Mary K; Richardson, Kris; Nalls, Mike A; Schulz, Christina-Alexandra; Liu, Yongmei; et al. (Mol Nutr Food Res, 2017)
SCOPE: Body weight responds variably to the intake of dairy foods. Genetic variation may contribute to inter-individual variability in associations between body weight and dairy consumption. METHODS AND RESULTS: A genome-wide interaction study to discover genetic variants that account for variation in BMI in the context of low-fat, high-fat and total dairy intake in cross-sectional analysis was conducted. Data from nine discovery studies (up to 25 513 European descent individuals) were meta-analyzed. Twenty-six genetic variants reached the selected significance threshold (p-interaction <10-7) , and six independent variants (LINC01512-rs7751666, PALM2/AKAP2-rs914359, ACTA2-rs1388, PPP1R12A-rs7961195, LINC00333-rs9635058, AC098847.1-rs1791355) were evaluated meta-analytically for replication of interaction in up to 17 675 individuals. Variant rs9635058 (128 kb 3' of LINC00333) was replicated (p-interaction = 0.004). In the discovery cohorts, rs9635058 interacted with dairy (p-interaction = 7.36 × 10-8) such that each serving of low-fat dairy was associated with 0.225 kg m-2 lower BMI per each additional copy of the effect allele (A). A second genetic variant (ACTA2-rs1388) approached interaction replication significance for low-fat dairy exposure. CONCLUSION: Body weight responses to dairy intake may be modified by genotype, in that greater dairy intake may protect a genetic subgroup from higher body weight.

Genome-wide meta-analysis associates HLA-DQA1/DRB1 and LPA and lifestyle factors with human longevity. - Joshi, Peter K; Pirastu, Nicola; Kentistou, Katherine A; Fischer, Krista; Hofer, Edith; Schraut, Katharina E; Clark, David W; Nutile, Teresa; Barnes, Catriona L K; Timmers, Paul R H J; Shen, Xia; Gandin, Ilaria; et al. (Nat Commun, 2017)
Genomic analysis of longevity offers the potential to illuminate the biology of human aging. Here, using genome-wide association meta-analysis of 606,059 parents' survival, we discover two regions associated with longevity (HLA-DQA1/DRB1 and LPA). We also validate previous suggestions that APOE, CHRNA3/5, CDKN2A/B, SH2B3 and FOXO3A influence longevity. Next we show that giving up smoking, educational attainment, openness to new experience and high-density lipoprotein (HDL) cholesterol levels are most positively genetically correlated with lifespan while susceptibility to coronary artery disease (CAD), cigarettes smoked per day, lung cancer, insulin resistance and body fat are most negatively correlated. We suggest that the effect of education on lifespan is principally mediated through smoking while the effect of obesity appears to act via CAD. Using instrumental variables, we suggest that an increase of one body mass index unit reduces lifespan by 7 months while 1 year of education adds 11 months to expected lifespan.Variability in human longevity is genetically influenced. Using genetic data of parental lifespan, the authors identify associations at HLA-DQA/DRB1 and LPA and find that genetic variants that increase educational attainment have a positive effect on lifespan whereas increasing BMI negatively affects lifespan.

{Genome-wide meta-analysis of 241,258 adults accounting for smoking behaviour identifies novel loci for obesity traits - Justice, A. E.; Winkler, T. W.; Feitosa, M. F.; Graff, M.; Fisher, V. A.; Young, K.; Barata, L.; Deng, X.; Czajkowski, J.; Hadley, D.; Ngwa, J. S.; Ahluwalia, T. S.; et al. (Nat Commun, 2017)
Few genome-wide association studies (GWAS) account for environmental exposures, like smoking, potentially impacting the overall trait variance when investigating the genetic contribution to obesity-related traits. Here, we use GWAS data from 51,080 current smokers and 190,178 nonsmokers (87% European descent) to identify loci influencing BMI and central adiposity, measured as waist circumference and waist-to-hip ratio both adjusted for BMI. We identify 23 novel genetic loci, and 9 loci with convincing evidence of gene-smoking interaction (GxSMK) on obesity-related traits. We show consistent direction of effect for all identified loci and significance for 18 novel and for 5 interaction loci in an independent study sample. These loci highlight novel biological functions, including response to oxidative stress, addictive behaviour, and regulatory functions emphasizing the importance of accounting for environment in genetic analyses. Our results suggest that tobacco smoking may alter the genetic susceptibility to overall adiposity and body fat distribution.

Genome-wide Trans-ethnic Meta-analysis Identifies Seven Genetic Loci Influencing Erythrocyte Traits and a Role for RBPMS in Erythropoiesis. - van Rooij, Frank J A; Qayyum, Rehan; Smith, Albert V; Zhou, Yi; Trompet, Stella; Tanaka, Toshiko; Keller, Margaux F; Chang, Li-Ching; Schmidt, Helena; Yang, Min-Lee; Chen, Ming-Huei; Hayes, James; et al. (Am J Hum Genet, 2017)
Genome-wide association studies (GWASs) have identified loci for erythrocyte traits in primarily European ancestry populations. We conducted GWAS meta-analyses of six erythrocyte traits in 71,638 individuals from European, East Asian, and African ancestries using a Bayesian approach to account for heterogeneity in allelic effects and variation in the structure of linkage disequilibrium between ethnicities. We identified seven loci for erythrocyte traits including a locus (RBPMS/GTF2E2) associated with mean corpuscular hemoglobin and mean corpuscular volume. Statistical fine-mapping at this locus pointed to RBPMS at this locus and excluded nearby GTF2E2. Using zebrafish morpholino to evaluate loss of function, we observed a strong in vivo erythropoietic effect for RBPMS but not for GTF2E2, supporting the statistical fine-mapping at this locus and demonstrating that RBPMS is a regulator of erythropoiesis. Our findings show the utility of trans-ethnic GWASs for discovery and characterization of genetic loci influencing hematologic traits.

Hidden heterogeneity in Alzheimer's disease: Insights from genetic association studies and other analyses. - Yashin, Anatoliy I; Fang, Fang; Kovtun, Mikhail; Wu, Deqing; Duan, Matt; Arbeev, Konstantin; Akushevich, Igor; Kulminski, Alexander; Culminskaya, Irina; Zhbannikov, Ilya; Yashkin, Arseniy; Stallard, Eric; et al. (Exp Gerontol, 2017)
Despite evident success in clarifying many important features of Alzheimer's disease (AD) the efficient methods of its prevention and treatment are not yet available. The reasons are likely to be the fact that AD is a multifactorial and heterogeneous health disorder with multiple alternative pathways of disease development and progression. The availability of genetic data on individuals participated in longitudinal studies of aging health and longevity, as well as on participants of cross-sectional case-control studies allow for investigating genetic and non-genetic connections with AD and to link the results of these analyses with research findings obtained in clinical, experimental, and molecular biological studies of this health disorder. The objective of this paper is to perform GWAS of AD in several study populations and investigate possible roles of detected genetic factors in developing AD hallmarks and in other health disorders. The data collected in the Framingham Heart Study (FHS), Cardiovascular Health Study (CHS), Health and Retirement Study (HRS) and Late Onset Alzheimer's Disease Family Study (LOADFS) were used in these analyses. The logistic regression and Cox's regression were used as statistical models in GWAS. The results of analyses confirmed strong associations of genetic variants from well-known genes APOE, TOMM40, PVRL2 (NECTIN2), and APOC1 with AD. Possible roles of these genes in pathological mechanisms resulting in development of hallmarks of AD are described. Many genes whose connection with AD was detected in other studies showed nominally significant associations with this health disorder in our study. The evidence on genetic connections between AD and vulnerability to infection, as well as between AD and other health disorders, such as cancer and type 2 diabetes, were investigated. The progress in uncovering hidden heterogeneity in AD would be substantially facilitated if common mechanisms involved in development of AD, its hallmarks, and AD related chronic conditions were investigated in their mutual connection.

Impact of common genetic determinants of Hemoglobin A1c on type 2 diabetes risk and diagnosis in ancestrally diverse populations: A transethnic genome-wide meta-analysis. - Wheeler, Eleanor; Leong, Aaron; Liu, Ching-Ti; Hivert, Marie-France; Strawbridge, Rona J; Podmore, Clara; Li, Man; Yao, Jie; Sim, Xueling; Hong, Jaeyoung; Chu, Audrey Y; Zhang, Weihua; et al. (PLoS Med, 2017)
BACKGROUND: Glycated hemoglobin (HbA1c) is used to diagnose type 2 diabetes (T2D) and assess glycemic control in patients with diabetes. Previous genome-wide association studies (GWAS) have identified 18 HbA1c-associated genetic variants. These variants proved to be classifiable by their likely biological action as erythrocytic (also associated with erythrocyte traits) or glycemic (associated with other glucose-related traits). In this study, we tested the hypotheses that, in a very large scale GWAS, we would identify more genetic variants associated with HbA1c and that HbA1c variants implicated in erythrocytic biology would affect the diagnostic accuracy of HbA1c. We therefore expanded the number of HbA1c-associated loci and tested the effect of genetic risk-scores comprised of erythrocytic or glycemic variants on incident diabetes prediction and on prevalent diabetes screening performance. Throughout this multiancestry study, we kept a focus on interancestry differences in HbA1c genetics performance that might influence race-ancestry differences in health outcomes. METHODS & FINDINGS: Using genome-wide association meta-analyses in up to 159,940 individuals from 82 cohorts of European, African, East Asian, and South Asian ancestry, we identified 60 common genetic variants associated with HbA1c. We classified variants as implicated in glycemic, erythrocytic, or unclassified biology and tested whether additive genetic scores of erythrocytic variants (GS-E) or glycemic variants (GS-G) were associated with higher T2D incidence in multiethnic longitudinal cohorts (N = 33,241). Nineteen glycemic and 22 erythrocytic variants were associated with HbA1c at genome-wide significance. GS-G was associated with higher T2D risk (incidence OR = 1.05, 95% CI 1.04-1.06, per HbA1c-raising allele, p = 3 × 10-29); whereas GS-E was not (OR = 1.00, 95% CI 0.99-1.01, p = 0.60). In Europeans and Asians, erythrocytic variants in aggregate had only modest effects on the diagnostic accuracy of HbA1c. Yet, in African Americans, the X-linked G6PD G202A variant (T-allele frequency 11%) was associated with an absolute decrease in HbA1c of 0.81%-units (95% CI 0.66-0.96) per allele in hemizygous men, and 0.68%-units (95% CI 0.38-0.97) in homozygous women. The G6PD variant may cause approximately 2% (N = 0.65 million, 95% CI 0.55-0.74) of African American adults with T2D to remain undiagnosed when screened with HbA1c. Limitations include the smaller sample sizes for non-European ancestries and the inability to classify approximately one-third of the variants. Further studies in large multiethnic cohorts with HbA1c, glycemic, and erythrocytic traits are required to better determine the biological action of the unclassified variants. CONCLUSIONS: As G6PD deficiency can be clinically silent until illness strikes, we recommend investigation of the possible benefits of screening for the G6PD genotype along with using HbA1c to diagnose T2D in populations of African ancestry or groups where G6PD deficiency is common. Screening with direct glucose measurements, or genetically-informed HbA1c diagnostic thresholds in people with G6PD deficiency, may be required to avoid missed or delayed diagnoses.
Keywords: Diabetes Mellitus, Type 2; Genetic Variation; Genome-Wide Association Study; Glycated Hemoglobin A; Humans; Phenotype; Risk

Incident atrial fibrillation and the risk of fracture in the cardiovascular health study. - Wallace, E R; Siscovick, D S; Sitlani, C M; Dublin, S; Mitchell, P; Robbins, J A; Fink, H A; Cauley, J A; Bůžková, P; Carbone, L; Chen, Z; Heckbert, S R (Osteoporos Int, 2017)
In this prospective cohort of 4462 older adults, incident atrial fibrillation (AF) was not statistically significantly associated with subsequent risk of incident fracture. INTRODUCTION: AF is associated with stroke, heart failure, dementia, and death, but its association with fracture is unknown. Therefore, we examined the association of incident AF with the risk of subsequent fracture in the Cardiovascular Health Study (CHS) cohort. METHODS: Of the CHS participants aged ≥65 years, 4462 were followed between 1991 and 2009, mean follow-up 8.8 years. Incident AF was identified by annual study electrocardiogram (ECG), hospital discharge diagnosis codes, or Medicare claims. Fractures of the hip, distal forearm, humerus, or pelvis were identified using hospital discharge diagnosis codes or Medicare claims. We used Cox proportional hazard models to estimate hazard ratios (HRs) and 95 % confidence intervals (CIs) for the association between incident AF (time-varying) and the risk of subsequent fracture. We also evaluated whether AF was associated with risk of sustaining a fall. RESULTS: Crude incident fracture rate was 22.9 per 1000 person-years in participants with AF and 17.7 per 1000 person-years in participants without AF. Individuals with incident AF were not at significantly higher risk of hip fracture (adjusted HR = 1.09, 95 % CI 0.83-1.42) or fracture at any selected site (adjusted HR = 0.97, 95 % CI 0.77-1.22) or risk of sustaining a fall (adjusted HR = 1.00, 95 % CI = 0.87-1.16) compared with those without AF. CONCLUSION: In this cohort of older, community-dwelling adults, incident AF was not shown to be associated with falls or hip or other fractures.

Large meta-analysis of genome-wide association studies identifies five loci for lean body mass. - Zillikens, M Carola; Demissie, Serkalem; Hsu, Yi-Hsiang; Yerges-Armstrong, Laura M; Chou, Wen-Chi; Stolk, Lisette; Livshits, Gregory; Broer, Linda; Johnson, Toby; Koller, Daniel L; Kutalik, Zoltán; Luan, Jian'an; et al. (Nat Commun, 2017)
Lean body mass, consisting mostly of skeletal muscle, is important for healthy aging. We performed a genome-wide association study for whole body (20 cohorts of European ancestry with n = 38,292) and appendicular (arms and legs) lean body mass (n = 28,330) measured using dual energy X-ray absorptiometry or bioelectrical impedance analysis, adjusted for sex, age, height, and fat mass. Twenty-one single-nucleotide polymorphisms were significantly associated with lean body mass either genome wide (p < 5 × 10-8) or suggestively genome wide (p < 2.3 × 10-6). Replication in 63,475 (47,227 of European ancestry) individuals from 33 cohorts for whole body lean body mass and in 45,090 (42,360 of European ancestry) subjects from 25 cohorts for appendicular lean body mass was successful for five single-nucleotide polymorphisms in/near HSD17B11, VCAN, ADAMTSL3, IRS1, and FTO for total lean body mass and for three single-nucleotide polymorphisms in/near VCAN, ADAMTSL3, and IRS1 for appendicular lean body mass. Our findings provide new insight into the genetics of lean body mass.Lean body mass is a highly heritable trait and is associated with various health conditions. Here, Kiel and colleagues perform a meta-analysis of genome-wide association studies for whole body lean body mass and find five novel genetic loci to be significantly associated.

Large-scale analyses of common and rare variants identify 12 new loci associated with atrial fibrillation. - Christophersen, Ingrid E; Rienstra, Michiel; Roselli, Carolina; Yin, Xiaoyan; Geelhoed, Bastiaan; Barnard, John; Lin, Honghuang; Arking, Dan E; Smith, Albert V; Albert, Christine M; Chaffin, Mark; Tucker, Nathan R; et al. (Nat Genet, 2017)
Atrial fibrillation affects more than 33 million people worldwide and increases the risk of stroke, heart failure, and death. Fourteen genetic loci have been associated with atrial fibrillation in European and Asian ancestry groups. To further define the genetic basis of atrial fibrillation, we performed large-scale, trans-ancestry meta-analyses of common and rare variant association studies. The genome-wide association studies (GWAS) included 17,931 individuals with atrial fibrillation and 115,142 referents; the exome-wide association studies (ExWAS) and rare variant association studies (RVAS) involved 22,346 cases and 132,086 referents. We identified 12 new genetic loci that exceeded genome-wide significance, implicating genes involved in cardiac electrical and structural remodeling. Our results nearly double the number of known genetic loci for atrial fibrillation, provide insights into the molecular basis of atrial fibrillation, and may facilitate the identification of new potential targets for drug discovery.

Large-Scale Cognitive GWAS Meta-Analysis Reveals Tissue-Specific Neural Expression and Potential Nootropic Drug Targets. - Lam, Max; Trampush, Joey W; Yu, Jin; Knowles, Emma; Davies, Gail; Liewald, David C; Starr, John M; Djurovic, Srdjan; Melle, Ingrid; Sundet, Kjetil; Christoforou, Andrea; Reinvang, Ivar; et al. (Cell Rep, 2017)
Here, we present a large (n = 107,207) genome-wide association study (GWAS) of general cognitive ability ("g"), further enhanced by combining results with a large-scale GWAS of educational attainment. We identified 70 independent genomic loci associated with general cognitive ability. Results showed significant enrichment for genes causing Mendelian disorders with an intellectual disability phenotype. Competitive pathway analysis implicated the biological processes of neurogenesis and synaptic regulation, as well as the gene targets of two pharmacologic agents: cinnarizine, a T-type calcium channel blocker, and LY97241, a potassium channel inhibitor. Transcriptome-wide and epigenome-wide analysis revealed that the implicated loci were enriched for genes expressed across all brain regions (most strongly in the cerebellum). Enrichment was exclusive to genes expressed in neurons but not oligodendrocytes or astrocytes. Finally, we report genetic correlations between cognitive ability and disparate phenotypes including psychiatric disorders, several autoimmune disorders, longevity, and maternal age at first birth.

Large-scale genome-wide analysis identifies genetic variants associated with cardiac structure and function. - Wild, Philipp S; Felix, Janine F; Schillert, Arne; Teumer, Alexander; Chen, Ming-Huei; Leening, Maarten J G; Völker, Uwe; Großmann, Vera; Brody, Jennifer A; Irvin, Marguerite R; Shah, Sanjiv J; Pramana, Setia; et al. (J Clin Invest, 2017)
BACKGROUND: Understanding the genetic architecture of cardiac structure and function may help to prevent and treat heart disease. This investigation sought to identify common genetic variations associated with inter-individual variability in cardiac structure and function. METHODS: A GWAS meta-analysis of echocardiographic traits was performed, including 46,533 individuals from 30 studies (EchoGen consortium). The analysis included 16 traits of left ventricular (LV) structure, and systolic and diastolic function. RESULTS: The discovery analysis included 21 cohorts for structural and systolic function traits (n = 32,212) and 17 cohorts for diastolic function traits (n = 21,852). Replication was performed in 5 cohorts (n = 14,321) and 6 cohorts (n = 16,308), respectively. Besides 5 previously reported loci, the combined meta-analysis identified 10 additional genome-wide significant SNPs: rs12541595 near MTSS1 and rs10774625 in ATXN2 for LV end-diastolic internal dimension; rs806322 near KCNRG, rs4765663 in CACNA1C, rs6702619 near PALMD, rs7127129 in TMEM16A, rs11207426 near FGGY, rs17608766 in GOSR2, and rs17696696 in CFDP1 for aortic root diameter; and rs12440869 in IQCH for Doppler transmitral A-wave peak velocity. Findings were in part validated in other cohorts and in GWAS of related disease traits. The genetic loci showed associations with putative signaling pathways, and with gene expression in whole blood, monocytes, and myocardial tissue. CONCLUSION: The additional genetic loci identified in this large meta-analysis of cardiac structure and function provide insights into the underlying genetic architecture of cardiac structure and warrant follow-up in future functional studies. FUNDING: For detailed information per study, see Acknowledgments.

Large-scale GWAS identifies multiple loci for hand grip strength providing biological insights into muscular fitness. - Willems, Sara M; Wright, Daniel J; Day, Felix R; Trajanoska, Katerina; Joshi, Peter K; Morris, John A; Matteini, Amy M; Garton, Fleur C; Grarup, Niels; Oskolkov, Nikolay; Thalamuthu, Anbupalam; Mangino, Massimo; et al. (Nat Commun, 2017)
Hand grip strength is a widely used proxy of muscular fitness, a marker of frailty, and predictor of a range of morbidities and all-cause mortality. To investigate the genetic determinants of variation in grip strength, we perform a large-scale genetic discovery analysis in a combined sample of 195,180 individuals and identify 16 loci associated with grip strength (P<5 × 10) in combined analyses. A number of these loci contain genes implicated in structure and function of skeletal muscle fibres (ACTG1), neuronal maintenance and signal transduction (PEX14, TGFA, SYT1), or monogenic syndromes with involvement of psychomotor impairment (PEX14, LRPPRC and KANSL1). Mendelian randomization analyses are consistent with a causal effect of higher genetically predicted grip strength on lower fracture risk. In conclusion, our findings provide new biological insight into the mechanistic underpinnings of grip strength and the causal role of muscular strength in age-related morbidities and mortality.

Low-Frequency Synonymous Coding Variation in CYP2R1 Has Large Effects on Vitamin D Levels and Risk of Multiple Sclerosis. - Manousaki, Despoina; Dudding, Tom; Haworth, Simon; Hsu, Yi-Hsiang; Liu, Ching-Ti; Medina-Gómez, Carolina; Voortman, Trudy; van der Velde, Nathalie; Melhus, Håkan; Robinson-Cohen, Cassianne; Cousminer, Diana L; Nethander, Maria; et al. (Am J Hum Genet, 2017)
Vitamin D insufficiency is common, correctable, and influenced by genetic factors, and it has been associated with risk of several diseases. We sought to identify low-frequency genetic variants that strongly increase the risk of vitamin D insufficiency and tested their effect on risk of multiple sclerosis, a disease influenced by low vitamin D concentrations. We used whole-genome sequencing data from 2,619 individuals through the UK10K program and deep-imputation data from 39,655 individuals genotyped genome-wide. Meta-analysis of the summary statistics from 19 cohorts identified in CYP2R1 the low-frequency (minor allele frequency = 2.5%) synonymous coding variant g.14900931G>A (p.Asp120Asp) (rs117913124[A]), which conferred a large effect on 25-hydroxyvitamin D (25OHD) levels (-0.43 SD of standardized natural log-transformed 25OHD per A allele; p value = 1.5 × 10(-88)). The effect on 25OHD was four times larger and independent of the effect of a previously described common variant near CYP2R1. By analyzing 8,711 individuals, we showed that heterozygote carriers of this low-frequency variant have an increased risk of vitamin D insufficiency (odds ratio [OR] = 2.2, 95% confidence interval [CI] = 1.78-2.78, p = 1.26 × 10(-12)). Individuals carrying one copy of this variant also had increased odds of multiple sclerosis (OR = 1.4, 95% CI = 1.19-1.64, p = 2.63 × 10(-5)) in a sample of 5,927 case and 5,599 control subjects. In conclusion, we describe a low-frequency CYP2R1 coding variant that exerts the largest effect upon 25OHD levels identified to date in the general European population and implicates vitamin D in the etiology of multiple sclerosis.
Keywords: Cholestanetriol 26-Monooxygenase; Cytochrome P450 Family 2; Gene Frequency; Genetic Predisposition to Disease; Genome, Human; Genome-Wide Association Study; Humans; Multiple Sclerosis; Polymorphism, Single Nucleotide; Risk Factors; Vitamin D; Vitamin D Deficiency

Measures of chronic kidney disease and risk of incident peripheral artery disease: a collaborative meta-analysis of individual participant data. - Matsushita, Kunihiro; Ballew, Shoshana H; Coresh, Josef; Arima, Hisatomi; Arnlöv, Johan; Cirillo, Massimo; Ebert, Natalie; Hiramoto, Jade S; Kimm, Heejin; Shlipak, Michael G; Visseren, Frank L J; Gansevoort, Ron T; et al. (Lancet Diabetes Endocrinol, 2017)
BACKGROUND: Some evidence suggests that chronic kidney disease is a risk factor for lower-extremity peripheral artery disease. We aimed to quantify the independent and joint associations of two measures of chronic kidney disease (estimated glomerular filtration rate [eGFR] and albuminuria) with the incidence of peripheral artery disease. METHODS: In this collaborative meta-analysis of international cohorts included in the Chronic Kidney Disease Prognosis Consortium (baseline measurements obtained between 1972 and 2014) with baseline measurements of eGFR and albuminuria, at least 1000 participants (this criterion not applied to cohorts exclusively enrolling patients with chronic kidney disease), and at least 50 peripheral artery disease events, we analysed adult participants without peripheral artery disease at baseline at the individual patient level with Cox proportional hazards models to quantify associations of creatinine-based eGFR, urine albumin-to-creatinine ratio (ACR), and dipstick proteinuria with the incidence of peripheral artery disease (including hospitalisation with a diagnosis of peripheral artery disease, intermittent claudication, leg revascularisation, and leg amputation). We assessed discrimination improvement through c-statistics. FINDINGS: We analysed 817 084 individuals without a history of peripheral artery disease at baseline from 21 cohorts. 18 261 cases of peripheral artery disease were recorded during follow-up across cohorts (median follow-up was 7·4 years [IQR 5·7-8·9], range 2·0-15·8 years across cohorts). Both chronic kidney disease measures were independently associated with the incidence of peripheral artery disease. Compared with an eGFR of 95 mL/min per 1·73 m2, adjusted hazard ratios (HRs) for incident study-specific peripheral artery disease was 1·22 (95% CI 1·14-1·30) at an eGFR of 45 mL/min per 1·73 m2 and 2·06 (1·70-2·48) at an eGFR of 15 mL/min per 1·73 m2. Compared with an ACR of 5 mg/g, the adjusted HR for incident study-specific peripheral artery disease was 1·50 (1·41-1·59) at an ACR of 30 mg/g and 2·28 (2·12-2·44) at an ACR of 300 mg/g. The adjusted HR at an ACR of 300 mg/g versus 5 mg/g was 3·68 (95% CI 3·00-4·52) for leg amputation. eGFR and albuminuria contributed multiplicatively (eg, adjusted HR 5·76 [4·90-6·77] for incident peripheral artery disease and 10·61 [5·70-19·77] for amputation in eGFR <30 mL/min per 1·73 m2 plus ACR ≥300 mg/g or dipstick proteinuria 2+ or higher vs eGFR ≥90 mL/min per 1·73 m2 plus ACR <10 mg/g or dipstick proteinuria negative). Both eGFR and ACR significantly improved peripheral artery disease risk discrimination beyond traditional predictors, with a substantial improvement prediction of amputation with ACR (difference in c-statistic 0·058, 95% CI 0·045-0·070). Patterns were consistent across clinical subgroups. INTERPRETATION: Even mild-to-moderate chronic kidney disease conferred increased risk of incident peripheral artery disease, with a strong association between albuminuria and amputation. Clinical attention should be paid to the development of peripheral artery disease symptoms and signs in people with any stage of chronic kidney disease. FUNDING: American Heart Association, US National Kidney Foundation, and US National Institute of Diabetes and Digestive and Kidney Diseases.

Multiancestry Study of Gene-Lifestyle Interactions for Cardiovascular Traits in 610 475 Individuals From 124 Cohorts: Design and Rationale. - Rao, D C; Sung, Yun J; Winkler, Thomas W; Schwander, Karen; Borecki, Ingrid; Cupples, L Adrienne; Gauderman, W James; Rice, Kenneth; Munroe, Patricia B; Psaty, Bruce M (Circ Cardiovasc Genet, 2017)
BACKGROUND: Several consortia have pursued genome-wide association studies for identifying novel genetic loci for blood pressure, lipids, hypertension, etc. They demonstrated the power of collaborative research through meta-analysis of study-specific results. METHODS AND RESULTS: The Gene-Lifestyle Interactions Working Group was formed to facilitate the first large, concerted, multiancestry study to systematically evaluate gene-lifestyle interactions. In stage 1, genome-wide interaction analysis is performed in 53 cohorts with a total of 149 684 individuals from multiple ancestries. In stage 2 involving an additional 71 cohorts with 460 791 individuals from multiple ancestries, focused analysis is performed for a subset of the most promising variants from stage 1. In all, the study involves up to 610 475 individuals. Current focus is on cardiovascular traits including blood pressure and lipids, and lifestyle factors including smoking, alcohol, education (as a surrogate for socioeconomic status), physical activity, psychosocial variables, and sleep. The total sample sizes vary among projects because of missing data. Large-scale gene-lifestyle or more generally gene-environment interaction (G×E) meta-analysis studies can be cumbersome and challenging. This article describes the design and some of the approaches pursued in the interaction projects. CONCLUSIONS: The Gene-Lifestyle Interactions Working Group provides an excellent framework for understanding the lifestyle context of genetic effects and to identify novel trait loci through analysis of interactions. An important and novel feature of our study is that the gene-lifestyle interaction (G×E) results may improve our knowledge about the underlying mechanisms for novel and already known trait loci.

New Blood Pressure-Associated Loci Identified in Meta-Analyses of 475 000 Individuals. - Kraja, Aldi T; Cook, James P; Warren, Helen R; Surendran, Praveen; Liu, Chunyu; Evangelou, Evangelos; Manning, Alisa K; Grarup, Niels; Drenos, Fotios; Sim, Xueling; Smith, Albert Vernon; Amin, Najaf; et al. (Circ Cardiovasc Genet, 2017)
BACKGROUND: Genome-wide association studies have recently identified >400 loci that harbor DNA sequence variants that influence blood pressure (BP). Our earlier studies identified and validated 56 single nucleotide variants (SNVs) associated with BP from meta-analyses of exome chip genotype data. An additional 100 variants yielded suggestive evidence of association. METHODS AND RESULTS: Here, we augment the sample with 140 886 European individuals from the UK Biobank, in whom 77 of the 100 suggestive SNVs were available for association analysis with systolic BP or diastolic BP or pulse pressure. We performed 2 meta-analyses, one in individuals of European, South Asian, African, and Hispanic descent (pan-ancestry, ≈475 000), and the other in the subset of individuals of European descent (≈423 000). Twenty-one SNVs were genome-wide significant (P<5×10-8) for BP, of which 4 are new BP loci: rs9678851 (missense, SLC4A1AP), rs7437940 (AFAP1), rs13303 (missense, STAB1), and rs1055144 (7p15.2). In addition, we identified a potentially independent novel BP-associated SNV, rs3416322 (missense, SYNPO2L) at a known locus, uncorrelated with the previously reported SNVs. Two SNVs are associated with expression levels of nearby genes, and SNVs at 3 loci are associated with other traits. One SNV with a minor allele frequency <0.01, (rs3025380 at DBH) was genome-wide significant. CONCLUSIONS: We report 4 novel loci associated with BP regulation, and 1 independent variant at an established BP locus. This analysis highlights several candidate genes with variation that alter protein function or gene expression for potential follow-up.

Novel Blood Pressure Locus and Gene Discovery Using Genome-Wide Association Study and Expression Data Sets From Blood and the Kidney. - Wain, Louise V; Vaez, Ahmad; Jansen, Rick; Joehanes, Roby; van der Most, Peter J; Erzurumluoglu, A Mesut; O'Reilly, Paul F; Cabrera, Claudia P; Warren, Helen R; Rose, Lynda M; Verwoert, Germaine C; Hottenga, Jouke-Jan; et al. (Hypertension, 2017)
Elevated blood pressure is a major risk factor for cardiovascular disease and has a substantial genetic contribution. Genetic variation influencing blood pressure has the potential to identify new pharmacological targets for the treatment of hypertension. To discover additional novel blood pressure loci, we used 1000 Genomes Project-based imputation in 150 134 European ancestry individuals and sought significant evidence for independent replication in a further 228 245 individuals. We report 6 new signals of association in or near HSPB7, TNXB, LRP12, LOC283335, SEPT9, and AKT2, and provide new replication evidence for a further 2 signals in EBF2 and NFKBIA Combining large whole-blood gene expression resources totaling 12 607 individuals, we investigated all novel and previously reported signals and identified 48 genes with evidence for involvement in blood pressure regulation that are significant in multiple resources. Three novel kidney-specific signals were also detected. These robustly implicated genes may provide new leads for therapeutic innovation.

{Novel genetic loci associated with hippocampal volume - Hibar, D. P.; Adams, H. H. H.; Jahanshad, N.; Chauhan, G.; Stein, J. L.; Hofer, E.; Renteria, M. E.; Bis, J. C.; Arias-Vasquez, A.; Ikram, M. K.; Desrivi?res, S.; Vernooij, M. W.; et al. (Nat Commun, 2017)
The hippocampal formation is a brain structure integrally involved in episodic memory, spatial navigation, cognition and stress responsiveness. Structural abnormalities in hippocampal volume and shape are found in several common neuropsychiatric disorders. To identify the genetic underpinnings of hippocampal structure here we perform a genome-wide association study (GWAS) of 33,536 individuals and discover six independent loci significantly associated with hippocampal volume, four of them novel. Of the novel loci, three lie within genes (ASTN2, DPP4 and MAST4) and one is found 200 kb upstream of SHH. A hippocampal subfield analysis shows that a locus within the MSRB3 gene shows evidence of a localized effect along the dentate gyrus, subiculum, CA1 and fissure. Further, we show that genetic variants associated with decreased hippocampal volume are also associated with increased risk for Alzheimer's disease (rg=-0.155). Our findings suggest novel biological pathways through which human genetic variation influences hippocampal volume and risk for neuropsychiatric illness.

Omega-3 Fatty Acids and Incident Ischemic Stroke and Its Atherothrombotic and Cardioembolic Subtypes in 3 US Cohorts. - Saber, Hamidreza; Yakoob, Mohammad Yawar; Shi, Peilin; Longstreth, W T; Lemaitre, Rozenn N; Siscovick, David; Rexrode, Kathryn M; Willett, Walter C; Mozaffarian, Dariush (Stroke, 2017)
BACKGROUND AND PURPOSE: The associations of individual long-chain n-3 polyunsaturated fatty acids with incident ischemic stroke and its main subtypes are not well established. We aimed to investigate prospectively the relationship of circulating eicosapentaenoic acid, docosapentaenoic acid (DPA), and docosahexaenoic acid (DHA) with risk of total ischemic, atherothrombotic, and cardioembolic stroke. METHODS: We measured circulating phospholipid fatty acids at baseline in 3 separate US cohorts: CHS (Cardiovascular Health Study), NHS (Nurses' Health Study), and HPFS (Health Professionals Follow-Up Study). Ischemic strokes were prospectively adjudicated and classified into atherothrombotic (large- and small-vessel infarctions) or cardioembolic by imaging studies and medical records. Risk according to fatty acid levels was assessed using Cox proportional hazards (CHS) or conditional logistic regression (NHS, HPFS) according to study design. Cohort findings were pooled using fixed-effects meta-analysis. RESULTS: A total of 953 incident ischemic strokes were identified (408 atherothrombotic, 256 cardioembolic, and 289 undetermined subtypes) during median follow-up of 11.2 years (CHS) and 8.3 years (pooled, NHS and HPFS). After multivariable adjustment, lower risk of total ischemic stroke was seen with higher DPA (highest versus lowest quartiles; pooled hazard ratio [HR], 0.74; 95% confidence interval [CI], 0.58-0.92) and DHA (HR, 0.80; 95% CI, 0.64-1.00) but not eicosapentaenoic acid (HR, 0.94; 95% CI, 0.77-1.19). DHA was associated with lower risk of atherothrombotic stroke (HR, 0.53; 95% CI, 0.34-0.83) and DPA with lower risk of cardioembolic stroke (HR, 0.58; 95% CI, 0.37-0.92). Findings in each individual cohort were consistent with pooled results. CONCLUSIONS: In 3 large US cohorts, higher circulating levels of DHA were inversely associated with incident atherothrombotic stroke and DPA with cardioembolic stroke. These novel findings suggest differential pathways of benefit for DHA, DPA, and eicosapentaenoic acid.
Keywords: Adult; Aged; Aged, 80 and over; Biomarkers; Brain Ischemia; Cardiovascular Diseases; Case-Control Studies; Cohort Studies; Fatty Acids, Omega-3; Female; Follow-Up Studies; Humans; Incidence; Intracranial Arteriosclerosis; Intracranial Embolism; Intracranial Thrombosis; Male; Middle Aged; Prospective Studies; Random Allocation; Risk Factors; Stroke; United States

PCSK9 Loss-of-Function Variants, Low-Density Lipoprotein Cholesterol, and Risk of Coronary Heart Disease and Stroke: Data From 9 Studies of Blacks and Whites. - Kent, Shia T; Rosenson, Robert S; Avery, Christy L; Chen, Yii-der I; Correa, Adolfo; Cummings, Steven R; Cupples, L Adrienne; Cushman, Mary; Evans, Daniel S; Gudnason, Vilmundur; Harris, Tamara B; Howard, George; et al. (Circ Cardiovasc Genet, 2017)
BACKGROUND: PCSK9 loss-of-function (LOF) variants allow for the examination of the effects of lifetime reduced low-density lipoprotein cholesterol (LDL-C) on cardiovascular events. We examined the association of PCSK9 LOF variants with LDL-C and incident coronary heart disease and stroke through a meta-analysis of data from 8 observational cohorts and 1 randomized trial of statin therapy. METHODS AND RESULTS: These 9 studies together included 17 459 blacks with 403 (2.3%) having at least 1 Y142X or C679X variant and 31 306 whites with 955 (3.1%) having at least 1 R46L variant. Unadjusted odds ratios for associations between PCSK9 LOF variants and incident coronary heart disease (851 events in blacks and 2662 events in whites) and stroke (523 events in blacks and 1660 events in whites) were calculated using pooled Mantel-Haenszel estimates with continuity correction factors. Pooling results across studies using fixed-effects inverse-variance-weighted models, PCSK9 LOF variants were associated with 35 mg/dL (95% confidence interval [CI], 32-39) lower LDL-C in blacks and 13 mg/dL (95% CI, 11-16) lower LDL-C in whites. PCSK9 LOF variants were associated with a pooled odds ratio for coronary heart disease of 0.51 (95% CI, 0.28-0.92) in blacks and 0.82 (95% CI, 0.63-1.06) in whites. PCSK9 LOF variants were not associated with incident stroke (odds ratio, 0.84; 95% CI, 0.48-1.47 in blacks and odds ratio, 1.06; 95% CI, 0.80-1.41 in whites). CONCLUSIONS: PCSK9 LOF variants were associated with lower LDL-C and coronary heart disease incidence. PCSK9 LOF variants were not associated with stroke risk.

Pharmacogenomics study of thiazide diuretics and QT interval in multi-ethnic populations: the cohorts for heart and aging research in genomic epidemiology. - Seyerle, A A; Sitlani, C M; Noordam, R; Gogarten, S M; Li, J; Li, X; Evans, D S; Sun, F; Laaksonen, M A; Isaacs, A; Kristiansson, K; Highland, H M; et al. (Pharmacogenomics J, 2017)
Thiazide diuretics, commonly used antihypertensives, may cause QT interval (QT) prolongation, a risk factor for highly fatal and difficult to predict ventricular arrhythmias. We examined whether common single-nucleotide polymorphisms (SNPs) modified the association between thiazide use and QT or its component parts (QRS interval, JT interval) by performing ancestry-specific, trans-ethnic and cross-phenotype genome-wide analyses of European (66%), African American (15%) and Hispanic (19%) populations (N=78 199), leveraging longitudinal data, incorporating corrected standard errors to account for underestimation of interaction estimate variances and evaluating evidence for pathway enrichment. Although no loci achieved genome-wide significance (P<5 × 10(-8)), we found suggestive evidence (P<5 × 10(-6)) for SNPs modifying the thiazide-QT association at 22 loci, including ion transport loci (for example, NELL1, KCNQ3). The biologic plausibility of our suggestive results and simulations demonstrating modest power to detect interaction effects at genome-wide significant levels indicate that larger studies and innovative statistical methods are warranted in future efforts evaluating thiazide-SNP interactions.The Pharmacogenomics Journal advance online publication, 18 July 2017; doi:10.1038/tpj.2017.10.

Predictors and outcomes of heart failure with mid-range ejection fraction. - Bhambhani, Vijeta; Kizer, Jorge R; Lima, João A C; van der Harst, Pim; Bahrami, Hossein; Nayor, Matthew; de Filippi, Christopher R; Enserro, Danielle; Blaha, Michael J; Cushman, Mary; Wang, Thomas J; Gansevoort, Ron T; et al. (Eur J Heart Fail, 2017)
AIMS: While heart failure with preserved (HFpEF) and reduced ejection fraction (HFrEF) are well described, determinants and outcomes of heart failure with mid-range ejection fraction (HFmrEF) remain unclear. We sought to examine clinical and biochemical predictors of incident HFmrEF in the community. METHODS AND RESULTS: We pooled data from four community-based longitudinal cohorts, with ascertainment of new heart failure (HF) classified into HFmrEF [ejection fraction (EF) 41-49%], HFpEF (EF ≥50%), and HFrEF (EF ≤40%). Predictors of incident HF subtypes were assessed using multivariable Cox models. Among 28 820 participants free of HF followed for a median of 12 years, there were 200 new HFmrEF cases, compared with 811 HFpEF and 1048 HFrEF. Clinical predictors of HFmrEF included age, male sex, systolic blood pressure, diabetes mellitus, and prior myocardial infarction (multivariable adjusted P ≤ 0.003 for all). Biomarkers that predicted HFmrEF included natriuretic peptides, cystatin-C, and high-sensitivity troponin (P ≤ 0.0004 for all). Natriuretic peptides were stronger predictors of HFrEF [hazard ratio (HR) 2.00 per 1 standard deviation increase, 95% confidence interval (CI) 1.81-2.20] than of HFmrEF (HR 1.51, 95% CI 1.20-1.90, P = 0.01 for difference), and did not differ in their association with incident HFmrEF and HFpEF (HR 1.56, 95% CI 1.41-1.73, P = 0.68 for difference). All-cause mortality following the onset of HFmrEF was worse than that of HFpEF (50 vs. 39 events per 1000 person-years, P = 0.02), but comparable to that of HFrEF (46 events per 1000 person-years, P = 0.78). CONCLUSIONS: We found overlap in predictors of incident HFmrEF with other HF subtypes. In contrast, mortality risk after HFmrEF was worse than HFpEF, and similar to HFrEF.

Rare coding variants in PLCG2, ABI3, and TREM2 implicate microglial-mediated innate immunity in Alzheimer's disease. - Sims, Rebecca; van der Lee, Sven J; Naj, Adam C; Bellenguez, Céline; Badarinarayan, Nandini; Jakobsdottir, Johanna; Kunkle, Brian W; Boland, Anne; Raybould, Rachel; Bis, Joshua C; Martin, Eden R; Grenier-Boley, Benjamin; et al. (Nat Genet, 2017)
We identified rare coding variants associated with Alzheimer's disease in a three-stage case-control study of 85,133 subjects. In stage 1, we genotyped 34,174 samples using a whole-exome microarray. In stage 2, we tested associated variants (P < 1 × 10-4) in 35,962 independent samples using de novo genotyping and imputed genotypes. In stage 3, we used an additional 14,997 samples to test the most significant stage 2 associations (P < 5 × 10-8) using imputed genotypes. We observed three new genome-wide significant nonsynonymous variants associated with Alzheimer's disease: a protective variant in PLCG2 (rs72824905: p.Pro522Arg, P = 5.38 × 10-10, odds ratio (OR) = 0.68, minor allele frequency (MAF)cases = 0.0059, MAFcontrols = 0.0093), a risk variant in ABI3 (rs616338: p.Ser209Phe, P = 4.56 × 10-10, OR = 1.43, MAFcases = 0.011, MAFcontrols = 0.008), and a new genome-wide significant variant in TREM2 (rs143332484: p.Arg62His, P = 1.55 × 10-14, OR = 1.67, MAFcases = 0.0143, MAFcontrols = 0.0089), a known susceptibility gene for Alzheimer's disease. These protein-altering changes are in genes highly expressed in microglia and highlight an immune-related protein-protein interaction network enriched for previously identified risk genes in Alzheimer's disease. These genetic findings provide additional evidence that the microglia-mediated innate immune response contributes directly to the development of Alzheimer's disease.
Keywords: Adaptor Proteins, Signal Transducing; Alzheimer Disease; Amino Acid Sequence; Case-Control Studies; Exome; Gene Expression Profiling; Gene Frequency; Genetic Predisposition to Disease; Genotype; Humans; Immunity, Innate; Linkage Disequilibrium; Membrane Glycoproteins; Microglia; Odds Ratio; Phospholipase C gamma; Polymorphism, Single Nucleotide; Protein Interaction Maps; Receptors, Immunologic; Sequence Homology, Amino Acid

REPEATED MEASUREMENTS OF BLOOD PRESSURE AND CHOLESTEROL IMPROVES CARDIOVASCULAR DISEASE RISK PREDICTION: AN INDIVIDUAL-PARTICIPANT-DATA META-ANALYSIS. - Paige, Ellie; Barrett, Jessica; Pennells, Lisa; Sweeting, Michael; Willeit, Peter; Di Angelantonio, Emanuele; Gudnason, Vilmundur; Nordestgaard, Børge G; Psaty, Bruce M; Goldbourt, Uri; Best, Lyle G; Assmann, Gerd; et al. (Am J Epidemiol, 2017)
The added value of incorporating information from repeated measurements of blood pressure and cholesterol for cardiovascular disease (CVD) risk prediction has not been rigorously assessed. We used data from the Emerging Risk Factors Collaboration on 191,445 adults (38 cohorts from across 17 countries with data from 1962-2014) with > 1 million measurements of systolic blood pressure, total cholesterol and high-density lipoprotein cholesterol; over a median 12 years of follow-up, 21,170 CVD events occurred. Risk prediction models using cumulative means of repeated measurements and summary measures from longitudinal modelling of the repeated measurements were compared to models using measurements from a single time point. Risk discrimination (C-index) and net reclassification were calculated, and changes in C-indices were meta-analysed across studies. Compared to the single time point model, the cumulative means and the longitudinal models increased the C-index by 0.0040 (95% CI: 0.0023, 0.0057) and 0.0023 (0.0005, 0.0042), respectively. Reclassification was also improved in both models; compared to the single time point model, overall net reclassification improvements were 0.0369 (0.0303, 0.0436) for the cumulative means model and 0.0177 (0.0110, 0.0243) for the longitudinal model. In conclusion, incorporating repeated measurements of blood pressure and cholesterol into CVD risk prediction models slightly improves risk prediction.

Short telomere length is associated with impaired cognitive performance in European ancestry cohorts. - Hägg, S; Zhan, Y; Karlsson, R; Gerritsen, L; Ploner, A; van der Lee, S J; Broer, L; Deelen, J; Marioni, R E; Wong, A; Lundquist, A; Zhu, G; et al. (Transl Psychiatry, 2017)
The association between telomere length (TL) dynamics on cognitive performance over the life-course is not well understood. This study meta-analyses observational and causal associations between TL and six cognitive traits, with stratifications on APOE genotype, in a Mendelian Randomization (MR) framework. Twelve European cohorts (N=17 052; mean age=59.2±8.8 years) provided results for associations between qPCR-measured TL (T/S-ratio scale) and general cognitive function, mini-mental state exam (MMSE), processing speed by digit symbol substitution test (DSST), visuospatial functioning, memory and executive functioning (STROOP). In addition, a genetic risk score (GRS) for TL including seven known genetic variants for TL was calculated, and used in associations with cognitive traits as outcomes in all cohorts. Observational analyses showed that longer telomeres were associated with better scores on DSST (β=0.051 per s.d.-increase of TL; 95% confidence interval (CI): 0.024, 0.077; P=0.0002), and MMSE (β=0.025; 95% CI: 0.002, 0.047; P=0.03), and faster STROOP (β=-0.053; 95% CI: -0.087, -0.018; P=0.003). Effects for DSST were stronger in APOE ɛ4 non-carriers (β=0.081; 95% CI: 0.045, 0.117; P=1.0 × 10-5), whereas carriers performed better in STROOP (β=-0.074; 95% CI: -0.140, -0.009; P=0.03). Causal associations were found for STROOP only (β=-0.598 per s.d.-increase of TL; 95% CI: -1.125, -0.072; P=0.026), with a larger effect in ɛ4-carriers (β=-0.699; 95% CI: -1.330, -0.069; P=0.03). Two-sample replication analyses using CHARGE summary statistics showed causal effects between TL and general cognitive function and DSST, but not with STROOP. In conclusion, we suggest causal effects from longer TL on better cognitive performance, where APOE ɛ4-carriers might be at differential risk.
Keywords: Adult; Aged; Apolipoprotein E4; Cognitive Dysfunction; Cohort Studies; European Continental Ancestry Group; Female; Genetic Carrier Screening; Genotype; Humans; Male; Mendelian Randomization Analysis; Middle Aged; Neuropsychological Tests; Psychometrics; Statistics as Topic; Telomere

Single-trait and multi-trait genome-wide association analyses identify novel loci for blood pressure in African-ancestry populations. - Liang, Jingjing; Le, Thu H; Edwards, Digna R Velez; Tayo, Bamidele O; Gaulton, Kyle J; Smith, Jennifer A; Lu, Yingchang; Jensen, Richard A; Chen, Guanjie; Yanek, Lisa R; Schwander, Karen; Tajuddin, Salman M; et al. (PLoS Genet, 2017)
Hypertension is a leading cause of global disease, mortality, and disability. While individuals of African descent suffer a disproportionate burden of hypertension and its complications, they have been underrepresented in genetic studies. To identify novel susceptibility loci for blood pressure and hypertension in people of African ancestry, we performed both single and multiple-trait genome-wide association analyses. We analyzed 21 genome-wide association studies comprised of 31,968 individuals of African ancestry, and validated our results with additional 54,395 individuals from multi-ethnic studies. These analyses identified nine loci with eleven independent variants which reached genome-wide significance (P < 1.25×10-8) for either systolic and diastolic blood pressure, hypertension, or for combined traits. Single-trait analyses identified two loci (TARID/TCF21 and LLPH/TMBIM4) and multiple-trait analyses identified one novel locus (FRMD3) for blood pressure. At these three loci, as well as at GRP20/CDH17, associated variants had alleles common only in African-ancestry populations. Functional annotation showed enrichment for genes expressed in immune and kidney cells, as well as in heart and vascular cells/tissues. Experiments driven by these findings and using angiotensin-II induced hypertension in mice showed altered kidney mRNA expression of six genes, suggesting their potential role in hypertension. Our study provides new evidence for genes related to hypertension susceptibility, and the need to study African-ancestry populations in order to identify biologic factors contributing to hypertension.
Keywords: African Americans; Animals; Basic Helix-Loop-Helix Transcription Factors; Blood Pressure; Cadherins; Case-Control Studies; Female; Genetic Loci; Genome-Wide Association Study; Humans; Hypertension; Male; Membrane Proteins; Mice; Multifactorial Inheritance; Polymorphism, Single Nucleotide

Soluble Inflammatory Markers and Risk of Incident Fractures in Older Adults: The Cardiovascular Health Study. - Stojanović, Danijela; Bůzková, Petra; Mukamal, Kenneth J; Heckbert, Susan R; Psaty, Bruce M; Fink, Howard A; Cauley, Jane A; Wallace, Erin; Curtis, Lesley H; Hirsch, Calvin; Budoff, Matthew; Li, Dong; et al. (J Bone Miner Res, 2017)
Several in vitro and animal studies have showed that inflammatory markers play a role in bone remodeling and pathogenesis of osteoporosis. Additionally, some human longitudinal studies showed suggestive associations between elevated inflammatory markers and increased risk of nontraumatic fractures. We examined several inflammatory markers and multiple fracture types in a single study of older individuals with extensive follow-up. We assessed the association of four inflammatory markers with the risk of incident hip fractures among 5265 participants of the Cardiovascular Health Study (CHS) and a composite endpoint of incident fractures of the hip, pelvis, humerus, or proximal forearm in 4477 participants. Among CHS participants followed between 1992 and 2009, we observed 480 incident hip fractures during a median follow-up of 11 years. In the composite fracture analysis cohort of 4477 participants, we observed 711 fractures during a median follow-up of 7 years. Adjusted hazard ratios (HRs) and 95% confidence intervals (CIs) for hip fracture associated with doubling of IL-6 were HR 1.15 (95% CI, 1.02 to 1.30) overall and HR 1.17 (95% CI, 1.01 to 1.35) in women. We also observed a positive association between each unit increase in white blood cell (WBC) count and risk of hip fracture: HR 1.04 (95% CI, 1.01 to 1.06) overall and HR 1.06 (95% CI, 0.95 to 1.20) in women. We observed no significant associations between any of the four inflammatory markers and a composite fracture endpoint. Our findings suggest that chronic inflammatory and immune processes may be related to higher rates of incident hip fractures. © 2017 American Society for Bone and Mineral Research.

Thyroid Function Within the Normal Range, Subclinical Hypothyroidism, and the Risk of Atrial Fibrillation. - Baumgartner, Christine; da Costa, Bruno R; Collet, Tinh-Hai; Feller, Martin; Floriani, Carmen; Bauer, Douglas C; Cappola, Anne R; Heckbert, Susan R; Ceresini, Graziano; Gussekloo, Jacobijn; den Elzen, Wendy P J; Peeters, Robin P; et al. (Circulation, 2017)
BACKGROUND: Atrial fibrillation (AF) is a highly prevalent disorder leading to heart failure, stroke, and death. Enhanced understanding of modifiable risk factors may yield opportunities for prevention. The risk of AF is increased in subclinical hyperthyroidism, but it is uncertain whether variations in thyroid function within the normal range or subclinical hypothyroidism are also associated with AF. METHODS: We conducted a systematic review and obtained individual participant data from prospective cohort studies that measured thyroid function at baseline and assessed incident AF. Studies were identified from MEDLINE and EMBASE databases from inception to July 27, 2016. The euthyroid state was defined as thyroid-stimulating hormone (TSH) 0.45 to 4.49 mIU/L, and subclinical hypothyroidism as TSH 4.5 to 19.9 mIU/L with free thyroxine (fT4) levels within reference range. The association of TSH levels in the euthyroid and subclinical hypothyroid range with incident AF was examined by using Cox proportional hazards models. In euthyroid participants, we additionally examined the association between fT4 levels and incident AF. RESULTS: Of 30 085 participants from 11 cohorts (278 955 person-years of follow-up), 1958 (6.5%) had subclinical hypothyroidism and 2574 individuals (8.6%) developed AF during follow-up. TSH at baseline was not significantly associated with incident AF in euthyroid participants or those with subclinical hypothyroidism. Higher fT4 levels at baseline in euthyroid individuals were associated with increased AF risk in age- and sex-adjusted analyses (hazard ratio, 1.45; 95% confidence interval, 1.26-1.66, for the highest quartile versus the lowest quartile of fT4; P for trend ≤0.001 across quartiles). Estimates did not substantially differ after further adjustment for preexisting cardiovascular disease. CONCLUSIONS: In euthyroid individuals, higher circulating fT4 levels, but not TSH levels, are associated with increased risk of incident AF.
Keywords: Adult; Aged; Aged, 80 and over; Asymptomatic Diseases; Atrial Fibrillation; Biomarkers; Chi-Square Distribution; Female; Humans; Hypothyroidism; Incidence; Male; Middle Aged; Predictive Value of Tests; Prognosis; Proportional Hazards Models; Risk Assessment; Risk Factors; Thyroid Function Tests; Thyroid Gland; Thyrotropin; Thyroxine; Time Factors; Young Adult

Trans-ethnic fine-mapping of genetic loci for body mass index in the diverse ancestral populations of the Population Architecture using Genomics and Epidemiology (PAGE) Study reveals evidence for multiple signals at established loci. - Fernandez-Rhodes, Lindsay; Gong, Jian; Haessler, Jeffrey; Franceschini, Nora; Graff, Mariaelisa; Nishimura, Katherine K; Wang, Yujie; Highland, Heather M; Yoneyama, Sachiko; Bush, William S; Goodloe, Robert; Ritchie, Marylyn D; et al. (Hum Genet, 2017)
Most body mass index (BMI) genetic loci have been identified in studies of primarily European ancestries. The effect of these loci in other racial/ethnic groups is less clear. Thus, we aimed to characterize the generalizability of 170 established BMI variants, or their proxies, to diverse US populations and trans-ethnically fine-map 36 BMI loci using a sample of >102,000 adults of African, Hispanic/Latino, Asian, European and American Indian/Alaskan Native descent from the Population Architecture using Genomics and Epidemiology Study. We performed linear regression of the natural log of BMI (18.5-70 kg/m(2)) on the additive single nucleotide polymorphisms (SNPs) at BMI loci on the MetaboChip (Illumina, Inc.), adjusting for age, sex, population stratification, study site, or relatedness. We then performed fixed-effect meta-analyses and a Bayesian trans-ethnic meta-analysis to empirically cluster by allele frequency differences. Finally, we approximated conditional and joint associations to test for the presence of secondary signals. We noted directional consistency with the previously reported risk alleles beyond what would have been expected by chance (binomial p < 0.05). Nearly, a quarter of the previously described BMI index SNPs and 29 of 36 densely-genotyped BMI loci on the MetaboChip replicated/generalized in trans-ethnic analyses. We observed multiple signals at nine loci, including the description of seven loci with novel multiple signals. This study supports the generalization of most common genetic loci to diverse ancestral populations and emphasizes the importance of dense multiethnic genomic data in refining the functional variation at genetic loci of interest and describing several loci with multiple underlying genetic variants.
Keywords: Body Mass Index; Ethnic Groups; Genetics, Population; Humans; Obesity

Trends in the incidence of dementia: design and methods in the Alzheimer Cohorts Consortium. - Chibnik, Lori B; Wolters, Frank J; Bäckman, Kristoffer; Beiser, Alexa; Berr, Claudine; Bis, Joshua C; Boerwinkle, Eric; Bos, Daniel; Brayne, Carol; Dartigues, Jean-François; Darweesh, Sirwan K L; Debette, Stephanie; et al. (Eur J Epidemiol, 2017)
Several studies have reported a decline in incidence of dementia which may have large implications for the projected burden of disease, and provide important guidance to preventive efforts. However, reports are conflicting or inconclusive with regard to the impact of gender and education with underlying causes of a presumed declining trend remaining largely unidentified. The Alzheimer Cohorts Consortium aggregates data from nine international population-based cohorts to determine changes in the incidence of dementia since 1990. We will employ Poisson regression models to calculate incidence rates in each cohort and Cox proportional hazard regression to compare 5-year cumulative hazards across study-specific epochs. Finally, we will meta-analyse changes per decade across cohorts, and repeat all analysis stratified by sex, education and APOE genotype. In all cohorts combined, there are data on almost 69,000 people at risk of dementia with the range of follow-up years between 2 and 27. The average age at baseline is similar across cohorts ranging between 72 and 77. Uniting a wide range of disease-specific and methodological expertise in research teams, the first analyses within the Alzheimer Cohorts Consortium are underway to tackle outstanding challenges in the assessment of time-trends in dementia occurrence.

Visit-to-Visit Blood Pressure Variability and Mortality and Cardiovascular Outcomes Among Older Adults: The Health, Aging, and Body Composition Study. - Wu, Chenkai; Shlipak, Michael G; Stawski, Robert S; Peralta, Carmen A; Psaty, Bruce M; Harris, Tamara B; Satterfield, Suzanne; Shiroma, Eric J; Newman, Anne B; Odden, Michelle C (Am J Hypertens, 2017)
BACKGROUND: Level of blood pressure (BP) is strongly associated with cardiovascular (CV) events and mortality. However, it is questionable whether mean BP can fully capture BP-related vascular risk. Increasing attention has been given to the value of visit-to-visit BP variability. METHODS: We examined the association of visit-to-visit BP variability with mortality, incident myocardial infarction (MI), and incident stroke among 1,877 well-functioning elders in the Health, Aging, and Body Composition Study. We defined visit-to-visit diastolic BP (DBP) and systolic BP (SBP) variability as the root-mean-square error of person-specific linear regression of BP as a function of time. Alternatively, we counted the number of considerable BP increases and decreases (separately; 10mm Hg for DBP and 20mm Hg for SBP) between consecutive visits for each individual. RESULTS: Over an average follow-up of 8.5 years, 623 deaths (207 from CV disease), 153 MIs, and 156 strokes occurred. The median visit-to-visit DBP and SBP variability was 4.96 mmHg and 8.53 mmHg, respectively. After multivariable adjustment, visit-to-visit DBP variability was related to higher all-cause (hazard ratio (HR) = 1.18 per 1 SD, 95% confidence interval (CI) = 1.01-1.37) and CV mortality (HR = 1.35, 95% CI = 1.05-1.73). Additionally, individuals having more considerable decreases of DBP (≥10mm Hg between 2 consecutive visits) had higher risk of all-cause (HR = 1.13, 95% CI = 0.99-1.28) and CV mortality (HR = 1.30, 95% CI = 1.05-1.61); considerable increases of SBP (≥20mm Hg) were associated with higher risk of all-cause (HR = 1.18, 95% CI = 1.03-1.36) and CV mortality (HR = 1.37, 95% CI = 1.08-1.74). CONCLUSIONS: Visit-to-visit DBP variability and considerable changes in DBP and SBP were risk factors for mortality in the elderly.
Keywords: Aged; Aging; Blood Pressure; Blood Pressure Determination; Body Composition; California; Cohort Studies; Female; Health Status; Humans; Hypertension; Incidence; Longitudinal Studies; Male; Myocardial Infarction; Office Visits; Prognosis; Retrospective Studies; Risk Factors; Stroke; Survival Rate

Association between subclinical thyroid dysfunction and change in bone mineral density in prospective cohorts. - Segna, D; Bauer, D C; Feller, M; Schneider, C; Fink, H A; Aubert, C E; Collet, T-H; da Costa, B R; Fischer, K; Peeters, R P; Cappola, A R; Blum, M R; et al. (J Intern Med, 2018)
BACKGROUND: Subclinical hyperthyroidism (SHyper) has been associated with increased risk of hip and other fractures, but the linking mechanisms remain unclear. OBJECTIVE: To investigate the association between subclinical thyroid dysfunction and bone loss. METHODS: Individual participant data analysis was performed after a systematic literature search in MEDLINE/EMBASE (1946-2016). Two reviewers independently screened and selected prospective cohorts providing baseline thyroid status and serial bone mineral density (BMD) measurements. We classified thyroid status as euthyroidism (thyroid-stimulating hormone [TSH] 0.45-4.49 mIU/L), SHyper (TSH < 0.45 mIU/L) and subclinical hypothyroidism (SHypo, TSH ≥ 4.50-19.99 mIU/L) both with normal free thyroxine levels. Our primary outcome was annualized percentage BMD change (%ΔBMD) from serial dual X-ray absorptiometry scans of the femoral neck, total hip and lumbar spine, obtained from multivariable regression in a random-effects two-step approach. RESULTS: Amongst 5458 individuals (median age 72 years, 49.1% women) from six prospective cohorts, 451 (8.3%) had SHypo and 284 (5.2%) had SHyper. During 36 569 person-years of follow-up, those with SHyper had a greater annual bone loss at the femoral neck versus euthyroidism: %ΔBMD = -0.18 (95% CI: -0.34, -0.02; I2 = 0%), with a nonstatistically significant pattern at the total hip: %ΔBMD = -0.14 (95% CI: -0.38, 0.10; I2 = 53%), but not at the lumbar spine: %ΔBMD = 0.03 (95% CI: -0.30, 0.36; I2 = 25%); especially participants with TSH < 0.10 mIU/L showed an increased bone loss in the femoral neck (%Δ BMD = -0.59; [95% CI: -0.99, -0.19]) and total hip region (%ΔBMD = -0.46 [95% CI: -1.05, -0.13]). In contrast, SHypo was not associated with bone loss at any site. CONCLUSION: Amongst adults, SHyper was associated with increased femoral neck bone loss, potentially contributing to the increased fracture risk.
Keywords: Aged; Asymptomatic Diseases; Bone Density; Female; Fractures, Bone; Humans; Hyperthyroidism; Hypothyroidism; Male; Risk Factors

Association of bone mineral density with hemoglobin and change in hemoglobin among older men and women: The Cardiovascular Health Study. - Valderrábano, Rodrigo J; Bůzková, Petra; Chang, Po-Yin; Zakai, Neil A; Fink, Howard A; Robbins, John A; Lee, Jennifer S; Wu, Joy Y (Bone, 2018)
PURPOSE: Osteoblasts and their precursors support hematopoiesis in the bone marrow. We hypothesized that declines in Hgb levels are associated with bone mineral density (BMD). METHODS: The Cardiovascular Health Study is a prospective longitudinal study that enrolled 5888 community-dwelling adults aged >65 years and measured hemoglobin twice, in 1989-90 and 1992-93, as well as BMD by dual-energy X-ray absorptiometry (DXA) in 1994-95. In a subset of 1513 men and women with a Hgb in 1992-93 and BMD, we used linear regression to estimate associations of Hgb (per standard deviation (SD)) with total hip (TH), lumbar spine (LS) and total body (TB) BMD, and used Poisson regression to estimate associations of anemia (in 1992-93; Hgb <13 g/dL in men; <12 g/dL in women) with "low BMD" defined as T-score less than -1 at the TH. In 1277 participants with Hgb measured on average 2.9 years apart and BMD, we used linear regression to estimate the associations of annualized change in Hgb with TH, LS and TB BMD. All models included age, sex, study-site, race, smoking, alcohol use, weight, height, steroid use, physical activity score, self-reported health, previous cardiovascular disease and prior anti-fracture medication use. RESULTS: No significant association was observed between Hgb, measured a mean 2.2 years prior to BMD, and BMD at the TH and LS in men (TH beta = -0.60 [x 10 g/cmper 1.1 g/dL Hgb], 95% CI: -1.88 to 0.68; LS beta = -1.69, 95% CI: -3.83 to 0.45) or women (TH beta = -0.49 [x 10 g/cmper 1.3 g/dL Hgb], 95% CI: -1.57 to 0.59; LS beta = -0.40, 95% CI: -2.57 to 1.76). Anemia was not observed to be significantly associated with low BMD in men (RR = 0.99, 95% CI: 0.72-1.40) nor women (RR = 0.98, 95% CI: 0.82-1.17). The mean change in Hgb was a loss of 0.06 g/dL/year (SD = 0.32). Change in Hgb was not observed to be significantly associated with BMD in men (TH beta = -0.55[x 10 g/cmper 1 g/dL annualized Hgb change], 95% CI: -4.28 to 3.19; LS beta = 0.63, 95% CI: -5.38 to 6.65) or women (TH beta = 0.92, 95% CI: -1.96 to 3.79; LS beta = -1.77, 95% CI: -7.52 to 3.98). No significant association was observed between anemia and low bone density by T-score in men and women. CONCLUSIONS: These findings support neither the hypothesis that low Hgb prior to bone density or decreases in Hgb are associated with bone density in older community-dwelling adults nor the use of Hgb level as a case-finding tool to prompt BMD measurement.

Association of Cardiovascular Biomarkers With Incident Heart Failure With Preserved and Reduced Ejection Fraction. - de Boer, Rudolf A; Nayor, Matthew; deFilippi, Christopher R; Enserro, Danielle; Bhambhani, Vijeta; Kizer, Jorge R; Blaha, Michael J; Brouwers, Frank P; Cushman, Mary; Lima, João A C; Bahrami, Hossein; van der Harst, Pim; et al. (JAMA Cardiol, 2018)
Importance: Nearly half of all patients with heart failure have preserved ejection fraction (HFpEF) as opposed to reduced ejection fraction (HFrEF), yet associations of biomarkers with future heart failure subtype are incompletely understood. Objective: To evaluate the associations of 12 cardiovascular biomarkers with incident HFpEF vs HFrEF among adults from the general population. Design, Setting, and Participants: This study included 4 longitudinal community-based cohorts: the Cardiovascular Health Study (1989-1990; 1992-1993 for supplemental African-American cohort), the Framingham Heart Study (1995-1998), the Multi-Ethnic Study of Atherosclerosis (2000-2002), and the Prevention of Renal and Vascular End-stage Disease study (1997-1998). Each cohort had prospective ascertainment of incident HFpEF and HFrEF. Data analysis was performed from June 25, 2015, to November 9, 2017. Exposures: The following biomarkers were examined: N-terminal pro B-type natriuretic peptide or brain natriuretic peptide, high-sensitivity troponin T or I, C-reactive protein (CRP), urinary albumin to creatinine ratio (UACR), renin to aldosterone ratio, D-dimer, fibrinogen, soluble suppressor of tumorigenicity, galectin-3, cystatin C, plasminogen activator inhibitor 1, and interleukin 6. Main Outcomes and Measures: Development of incident HFpEF and incident HFrEF. Results: Among the 22 756 participants in these 4 cohorts (12 087 women and 10 669 men; mean [SD] age, 60 [13] years) in the study, during a median follow-up of 12 years, 633 participants developed incident HFpEF, and 841 developed HFrEF. In models adjusted for clinical risk factors of heart failure, 2 biomarkers were significantly associated with incident HFpEF: UACR (hazard ratio [HR], 1.33; 95% CI, 1.20-1.48; P < .001) and natriuretic peptides (HR, 1.27; 95% CI, 1.16-1.40; P < .001), with suggestive associations for high-sensitivity troponin (HR, 1.11; 95% CI, 1.03-1.19; P = .008), plasminogen activator inhibitor 1 (HR, 1.22; 95% CI, 1.03-1.45; P = .02), and fibrinogen (HR, 1.12; 95% CI, 1.03-1.22; P = .01). By contrast, 6 biomarkers were associated with incident HFrEF: natriuretic peptides (HR, 1.54; 95% CI, 1.41-1.68; P < .001), UACR (HR, 1.21; 95% CI, 1.11-1.32; P < .001), high-sensitivity troponin (HR, 1.37; 95% CI, 1.29-1.46; P < .001), cystatin C (HR, 1.19; 95% CI, 1.11-1.27; P < .001), D-dimer (HR, 1.22; 95% CI, 1.11-1.35; P < .001), and CRP (HR, 1.19; 95% CI, 1.11-1.28; P < .001). When directly compared, natriuretic peptides, high-sensitivity troponin, and CRP were more strongly associated with HFrEF compared with HFpEF. Conclusions and Relevance: Biomarkers of renal dysfunction, endothelial dysfunction, and inflammation were associated with incident HFrEF. By contrast, only natriuretic peptides and UACR were associated with HFpEF. These findings highlight the need for future studies focused on identifying novel biomarkers of the risk of HFpEF.

Association of Frailty with Recovery from Disability among Community-Dwelling Older Adults: Results from Two Large U.S. Cohorts. - Wu, Chenkai; Kim, Dae H; Xue, Qian-Li; Lee, David S H; Varadhan, Ravi; Odden, Michelle C (J Gerontol A Biol Sci Med Sci, 2018)
Background: Disability in activities of daily living (ADLs) is a dynamic process and transitions among different disability states are common. However, little is known about factors affecting recovery from disability. We examined the association between frailty and recovery from disability among non-disabled community-dwelling elders. Methods: We studied 1023 adults from the Cardiovascular Health Study (CHS) and 685 adults from the Health and Retirement Study (HRS), who were ≥65 years and had incident disability, defined as having difficulty in ≥1 ADL (dressing, eating, toileting, bathing, transferring, walking across a room). Disability recovery was defined as having no difficulty in any ADLs. Frailty was assessed by slowness, weakness, exhaustion, inactivity, and shrinking. Persons were classified as "non-frail" (0 criteria), "prefrail" (1-2 criteria), or "frail" (3-5 criteria). Results: In total, 539 (52.7%) CHS participants recovered from disability within one year. Almost two-thirds of non-frail persons recovered, while less than two-fifths of the frail recovered. In the HRS, 234 (34.2%) participants recovered from disability within two years. Approximately half of the non-frail recovered, while less than one-fifth of the frail recovered. After adjustment, prefrail and frail CHS participants were 16% and 36% less likely to recover than the non-frail, respectively. In the HRS, frail persons had a 41% lower likelihood of recovery than the non-frail. Conclusions: Frailty is an independent predictor of poor recovery from disability among non-disabled older adults. These findings validate frailty as a marker of decreased resilience and may offer opportunities for individualized interventions and geriatric care based on frailty assessment.

The Association of Obesity and Cardiometabolic Traits With Incident HFpEF and HFrEF. - Savji, Nazir; Meijers, Wouter C; Bartz, Traci M; Bhambhani, Vijeta; Cushman, Mary; Nayor, Matthew; Kizer, Jorge R; Sarma, Amy; Blaha, Michael J; Gansevoort, Ron T; Gardin, Julius M; Hillege, Hans L; et al. (JACC Heart Fail, 2018)
OBJECTIVES: This study evaluated the associations of obesity and cardiometabolic traits with incident heart failure with preserved versus reduced ejection fraction (HFpEF vs. HFrEF). Given known sex differences in HF subtype, we examined men and women separately. BACKGROUND: Recent studies suggest that obesity confers greater risk of HFpEF versus HFrEF. Contributions of associated metabolic traits to HFpEF are less clear. METHODS: We studied 22,681 participants from 4 community-based cohorts followed for incident HFpEF versus HFrEF (ejection fraction ≥50% vs. <50%). We evaluated the association of body mass index (BMI) and cardiometabolic traits with incident HF subtype using Cox models. RESULTS: The mean age was 60 ± 13 years, and 53% were women. Over a median follow-up of 12 years, 628 developed incident HFpEF and 835 HFrEF. Greater BMI portended higher risk of HFpEF compared with HFrEF (hazard ratio [HR]: 1.34 per 1-SD increase in BMI; 95% confidence interval [CI]: 1.24 to 1.45 vs. HR: 1.18; 95% CI: 1.10 to 1.27). Similarly, insulin resistance (homeostatic model assessment of insulin resistance) was associated with HFpEF (HR: 1.20 per 1-SD; 95% CI: 1.05 to 1.37), but not HFrEF (HR: 0.99; 95% CI: 0.88 to 1.11; p < 0.05 for difference HFpEF vs. HFrEF). We found that the differential association of BMI with HFpEF versus HFrEF was more pronounced among women (p for difference HFpEF vs. HFrEF = 0.01) when compared with men (p = 0.34). CONCLUSIONS: Obesity and related cardiometabolic traits including insulin resistance are more strongly associated with risk of future HFpEF versus HFrEF. The differential risk of HFpEF with obesity seems particularly pronounced among women and may underlie sex differences in HF subtypes.

Atrial fibrillation in an African-American cohort: The Jackson Heart Study. - Austin, Thomas R; Wiggins, Kerri L; Blackshear, Chad; Yang, Yi; Benjamin, Emelia J; Curtis, Lesley H; Sotoodehnia, Nona; Correa, Adolfo; Heckbert, Susan R (Clin Cardiol, 2018)
BACKGROUND: Atrial fibrillation (AF) is an important public health problem across race/ethnic groups. Data from US cohort studies initiated in the 1980s suggest a higher prevalence of AF risk factors among African-Americans (AAs) than whites, but lower AF incidence. The Jackson Heart Study (JHS) is a community-based study of 5306 AAs recruited starting in 2000. HYPOTHESIS: Demographic, anthropometric, cardiovascular, and/or electrocardiographic factors are associated with AF incidence in JHS. METHODS: Using baseline participant characteristics and incident AF identified through hospital surveillance, study electrocardiogram, and Medicare claims, we estimated age- and sex-specific AF incidence rates, compared them with rates in AA participants in the Multi-Ethnic Study of Atherosclerosis (MESA) and Cardiovascular Health Study (CHS), and examined associations of cardiovascular risk factors with AF. RESULTS: A total of 66 participants had prevalent AF at baseline. Over an average follow-up of 8.5 years, 242 cases of incident AF were identified. Age- and sex-specific AF incidence rates in JHS were similar to those among AAs in MESA and appeared slightly lower than those among AAs in CHS. In an age- and sex-adjusted model, associations with incident AF were observed for modifiable risk factors: high body weight (HR = 1.23 per 15 kg, 95%CI 1.13-1.35), systolic blood pressure (HR = 1.29 per 20 mmHg, 95%CI 1.13-1.47), and current smoking (HR = 1.80, 95%CI 1.27-2.55). Risk estimates associated with these risk factors were only slightly attenuated after multivariable adjustments. CONCLUSIONS: These findings underscore the potential additional benefits of interventions for weight management, control of hypertension, and smoking cessation for the prevention of AF among AAs.

Biochemical Markers of Bone Turnover and Risk of Incident Diabetes in Older Women: The Cardiovascular Health Study. - Massera, Daniele; Biggs, Mary L; Walker, Marcella D; Mukamal, Kenneth J; Ix, Joachim H; Djoussé, Luc; Valderrábano, Rodrigo J; Siscovick, David S; Tracy, Russell P; Xue, XiaoNan; Kizer, Jorge R (Diabetes Care, 2018)
OBJECTIVE: To investigate the relationship of osteocalcin (OC), a marker of bone formation, and C-terminal cross-linked telopeptide of type I collagen (CTX), a marker of bone resorption, with incident diabetes in older women. RESEARCH DESIGN AND METHODS: The analysis included 1,455 female participants from the population-based Cardiovascular Health Study (CHS) (mean [SD] age 74.6 [5.0] years). The cross-sectional association of serum total OC and CTX levels with insulin resistance (HOMA-IR) was examined using multiple linear regression. The longitudinal association of both markers with incident diabetes, defined by follow-up glucose measurements, medications, and ICD-9 codes, was examined using multivariable Cox proportional hazards models. RESULTS: OC and CTX were strongly correlated ( = 0.80). In cross-sectional analyses, significant or near-significant inverse associations with HOMA-IR were observed for continuous levels of OC (β = -0.12 per SD increment; = 0.004) and CTX (β = -0.08 per SD; = 0.051) after full adjustment for demographic, lifestyle, and clinical covariates. During a median follow-up of 11.5 years, 196 cases of incident diabetes occurred. After full adjustment, both biomarkers exhibited inverse associations with incident diabetes (OC: hazard ratio 0.85 per SD [95% CI 0.71-1.02; = 0.075]; CTX: 0.82 per SD [0.69-0.98; = 0.031]), associations that were comparable in magnitude and approached or achieved statistical significance. CONCLUSIONS: In late postmenopausal women, lower OC and CTX levels were associated with similarly increased risks of insulin resistance at baseline and incident diabetes over long-term follow-up. Further research to delineate the mechanisms linking abnormal bone homeostasis and energy metabolism could uncover new approaches for the prevention of these age-related disorders.

Common and Rare Coding Genetic Variation Underlying the Electrocardiographic PR Interval. - Lin, Honghuang; van Setten, Jessica; Smith, Albert V; Bihlmeyer, Nathan A; Warren, Helen R; Brody, Jennifer A; Radmanesh, Farid; Hall, Leanne; Grarup, Niels; Müller-Nurasyid, Martina; Boutin, Thibaud; Verweij, Niek; et al. (Circ Genom Precis Med, 2018)
BACKGROUND: Electrical conduction from the cardiac sinoatrial node to the ventricles is critical for normal heart function. Genome-wide association studies have identified more than a dozen common genetic loci that are associated with PR interval. However, it is unclear whether rare and low-frequency variants also contribute to PR interval heritability. METHODS: We performed large-scale meta-analyses of the PR interval that included 83 367 participants of European ancestry and 9436 of African ancestry. We examined both common and rare variants associated with the PR interval. RESULTS: We identified 31 genetic loci that were significantly associated with PR interval after Bonferroni correction (<1.2×10), including 11 novel loci that have not been reported previously. Many of these loci are involved in heart morphogenesis. In gene-based analysis, we found that multiple rare variants at (=5.9×10) and (=1.1×10) were associated with PR interval. locus also was implicated in the common variant analysis, whereas was a novel locus. CONCLUSIONS: We identified common variants at 11 novel loci and rare variants within 2 gene regions that were significantly associated with PR interval. Our findings provide novel insights to the current understanding of atrioventricular conduction, which is critical for cardiac activity and an important determinant of health.

A comprehensive evaluation of the genetic architecture of sudden cardiac arrest. - Ashar, Foram N; Mitchell, Rebecca N; Albert, Christine M; Newton-Cheh, Christopher; Brody, Jennifer A; Müller-Nurasyid, Martina; Moes, Anna; Meitinger, Thomas; Mak, Angel; Huikuri, Heikki; Junttila, M Juhani; Goyette, Philippe; et al. (Eur Heart J, 2018)
Aims: Sudden cardiac arrest (SCA) accounts for 10% of adult mortality in Western populations. We aim to identify potential loci associated with SCA and to identify risk factors causally associated with SCA. Methods and results: We carried out a large genome-wide association study (GWAS) for SCA (n = 3939 cases, 25 989 non-cases) to examine common variation genome-wide and in candidate arrhythmia genes. We also exploited Mendelian randomization (MR) methods using cross-trait multi-variant genetic risk score associations (GRSA) to assess causal relationships of 18 risk factors with SCA. No variants were associated with SCA at genome-wide significance, nor were common variants in candidate arrhythmia genes associated with SCA at nominal significance. Using cross-trait GRSA, we established genetic correlation between SCA and (i) coronary artery disease (CAD) and traditional CAD risk factors (blood pressure, lipids, and diabetes), (ii) height and BMI, and (iii) electrical instability traits (QT and atrial fibrillation), suggesting aetiologic roles for these traits in SCA risk. Conclusions: Our findings show that a comprehensive approach to the genetic architecture of SCA can shed light on the determinants of a complex life-threatening condition with multiple influencing factors in the general population. The results of this genetic analysis, both positive and negative findings, have implications for evaluating the genetic architecture of patients with a family history of SCA, and for efforts to prevent SCA in high-risk populations and the general community.

{Dairy Consumption and Body Mass Index Among Adults: Mendelian Randomization Analysis of 184802 Individuals from 25 Studies - Huang, T.; Ding, M.; Bergholdt, H. K. M.; Wang, T.; Heianza, Y.; Sun, D.; Frazier-Wood, A. C.; Aslibekyan, S.; North, K. E.; Voortman, T.; Graff, M.; Smith, C. E.; et al. (Clin Chem, 2018)
Associations between dairy intake and body mass index (BMI) have been inconsistently observed in epidemiological studies, and the causal relationship remains ill defined.\ We performed Mendelian randomization (MR) analysis using an established dairy intake-associated genetic polymorphism located upstream of the lactase gene (LCT-13910 C/T, rs4988235) as an instrumental variable (IV). Linear regression models were fitted to analyze associations between (a) dairy intake and BMI, (b) rs4988235 and dairy intake, and (c) rs4988235 and BMI in each study. The causal effect of dairy intake on BMI was quantified by IV estimators among 184802 participants from 25 studies.\ Higher dairy intake was associated with higher BMI (β = 0.03 kg/m2 per serving/day; 95% CI, 0.00-0.06; P = 0.04), whereas the LCT genotype with 1 or 2 T allele was significantly associated with 0.20 (95% CI, 0.14-0.25) serving/day higher dairy intake (P = 3.15 × 10-12) and 0.12 (95% CI, 0.06-0.17) kg/m2 higher BMI (P = 2.11 × 10-5). MR analysis showed that the genetically determined higher dairy intake was significantly associated with higher BMI (β = 0.60 kg/m2 per serving/day; 95% CI, 0.27-0.92; P = 3.0 × 10-4).\ The present study provides strong evidence to support a causal effect of higher dairy intake on increased BMI among adults.

Demographic-Specific Rates for Life Events in the Cardiovascular Health Study and Comparisons With Other Studies. - Vitaliano, Peter P; Fitzpatrick, Annette L; Williams, Lee E; Montano, Michalina A; Russo, Joan E (Innov Aging, 2018)
Purpose of the Study: (1a) We use the Cardiovascular Health Study (CHS), a multi-site heterogeneous sample of Medicare enrollees ( = 5,849) to provide rates for specific life events experienced within 6 months; (1b) We present rates for 29 other studies of community-residing older adults ( = 41,308); (2) For the CHS, we provide demographic-specific rates and predicted probabilities for age [young-old (65-75) vs old-old (≥75)], gender, race, marital status, and education. Design/Methods: The CHS sample is 57.6% women, 84.2% white (15.8% black), and 66.3% married. Mean age is 72.8 years (standard deviation [] = 5.6, range = 65-100) and education is 13.7 years ( = 4.8). Life events were interviewer-assessed. Regressions estimated associations of life event rates with demographic groups (e.g., age), controlling for other demographic variables (e.g., gender, etc.). Results: (1a) CHS rates ranged from 44.7% (death of someone close) to 1.1% (retirement/work changes). (1b) Most life event studies used total scores and only 5 that met our inclusion criteria used time intervals <1 year; longer intervals were associated with higher rates. (2) In the CHS, the life event for illnesses was related to 5 demographic variables (net the other 4 demographic variables), difficulties caregiving to 4, and worse relationships to 3 demographic variables. Race was related to 8 life events, marital status to 7, education to 6, and age to 4 events. Implications: By identifying demographic groups at highest risk for life events, this research focuses on older adults at greatest risk for health problems. These data are necessary for translating research into interventions, practice, and policy.

Development, Construct Validity, and Predictive Validity of a Continuous Frailty Scale: Results from Two Large U.S. Cohorts. - Wu, Chenkai; Geldhof, G John; Xue, Qian-Li; Kim, Dae H; Newman, Anne B; Odden, Michelle C (Am J Epidemiol, 2018)
Frailty is an age-related clinical syndrome of decreased resilience to stressors. Among numerous assessments of frailty, the frailty phenotype (FP) scale, proposed by Fried and colleagues has been the most widely used one. We aimed to develop a continuous frailty scale that may overcome limitations facing the categorical FP scale and to evaluate its construct validity, predictive validity, and measurement properties. Data were from the Cardiovascular Health Study (N = 4243) and Health and Retirement Study (N = 7600). Frailty was conceptualized as a continuous construct, measured by five measures used in FP scale: gait speed, grip strength, exhaustion, physical activity, and weight loss. We used confirmatory factor analysis to investigate the relationship between five indicators and the latent frailty construct. We examined the association of the continuous frailty scale with mortality and disability. The unidimensional model fit the data satisfactorily; similar factor structure was observed across two cohorts. Gait speed and weight loss were the strongest and weakest indicators, respectively; grip strength, exhaustion, and physical activity had similar strength in measuring frailty. In each cohort, the continuous frailty scale was strongly associated with mortality and disability and persisted to be associated with outcomes among robust and prefrail persons classified by the FP scale.

DNA methylation age is associated with an altered hemostatic profile in a multi-ethnic meta-analysis. - Ward-Caviness, Cavin K; Huffman, Jennifer E; Evertt, Karl; Germain, Marine; van Dongen, Jenny; Hill, W David; Jhun, Min A; Brody, Jennifer A; Ghanbari, Mohsen; Du, Lei; Roetker, Nicholas S; de Vries, Paul S; et al. (Blood, 2018)
Many hemostatic factors are associated with age and age-related diseases, however much remains unknown about the biological mechanisms linking aging and hemostatic factors. DNA methylation is a novel means by which to assess epigenetic aging, which is a measure of age and the aging processes as determined by altered epigenetic states. We used a meta-analysis approach to examine the association between measures of epigenetic aging and hemostatic factors, as well as a clotting time measure. For fibrinogen, we used European and African-ancestry participants who were meta-analyzed separately and combined via a random effects meta-analysis. All other measures only included participants of European-ancestry. We found that 1-year higher extrinsic epigenetic age as compared to chronological age was associated with higher fibrinogen (0.004 g/L per year; 95% CI: 0.001, 0.007; P = 0.01) and plasminogen activator inhibitor 1 (PAI-1; 0.13 U/mL per year; 95% CI: 0.07, 0.20; P = 6.6x10-5) concentrations as well as lower activated partial thromboplastin time, a measure of clotting time. We replicated PAI-1 associations using an independent cohort. To further elucidate potential functional mechanisms we associated epigenetic aging with expression levels of the PAI-1 protein encoding gene (SERPINE1) and the three fibrinogen subunit-encoding genes (FGA, FGG, and FGB), in both peripheral blood and aorta intima-media samples. We observed associations between accelerated epigenetic aging and transcription of FGG in both tissues. Collectively, our results indicate that accelerated epigenetic aging is associated with a pro-coagulation hemostatic profile, and that epigenetic aging may regulate hemostasis in part via gene transcription.

Equalization of four cardiovascular risk algorithms after systematic recalibration: individual-participant meta-analysis of 86 prospective studies. - Pennells, Lisa; Kaptoge, Stephen; Wood, Angela; Sweeting, Mike; Zhao, Xiaohui; White, Ian; Burgess, Stephen; Willeit, Peter; Bolton, Thomas; Moons, Karel G M; van der Schouw, Yvonne T; Selmer, Randi; et al. (Eur Heart J, 2018)
Aims: There is debate about the optimum algorithm for cardiovascular disease (CVD) risk estimation. We conducted head-to-head comparisons of four algorithms recommended by primary prevention guidelines, before and after 'recalibration', a method that adapts risk algorithms to take account of differences in the risk characteristics of the populations being studied. Methods and results: Using individual-participant data on 360 737 participants without CVD at baseline in 86 prospective studies from 22 countries, we compared the Framingham risk score (FRS), Systematic COronary Risk Evaluation (SCORE), pooled cohort equations (PCE), and Reynolds risk score (RRS). We calculated measures of risk discrimination and calibration, and modelled clinical implications of initiating statin therapy in people judged to be at 'high' 10 year CVD risk. Original risk algorithms were recalibrated using the risk factor profile and CVD incidence of target populations. The four algorithms had similar risk discrimination. Before recalibration, FRS, SCORE, and PCE over-predicted CVD risk on average by 10%, 52%, and 41%, respectively, whereas RRS under-predicted by 10%. Original versions of algorithms classified 29-39% of individuals aged ≥40 years as high risk. By contrast, recalibration reduced this proportion to 22-24% for every algorithm. We estimated that to prevent one CVD event, it would be necessary to initiate statin therapy in 44-51 such individuals using original algorithms, in contrast to 37-39 individuals with recalibrated algorithms. Conclusion: Before recalibration, the clinical performance of four widely used CVD risk algorithms varied substantially. By contrast, simple recalibration nearly equalized their performance and improved modelled targeting of preventive action to clinical need.

Exome Chip Analysis Identifies Low-Frequency and Rare Variants in for White Matter Hyperintensities on Brain Magnetic Resonance Imaging. - Jian, Xueqiu; Satizabal, Claudia L; Smith, Albert V; Wittfeld, Katharina; Bis, Joshua C; Smith, Jennifer A; Hsu, Fang-Chi; Nho, Kwangsik; Hofer, Edith; Hagenaars, Saskia P; Nyquist, Paul A; Mishra, Aniket; et al. (Stroke, 2018)
BACKGROUND AND PURPOSE: White matter hyperintensities (WMH) on brain magnetic resonance imaging are typical signs of cerebral small vessel disease and may indicate various preclinical, age-related neurological disorders, such as stroke. Though WMH are highly heritable, known common variants explain a small proportion of the WMH variance. The contribution of low-frequency/rare coding variants to WMH burden has not been explored. METHODS: In the discovery sample we recruited 20 719 stroke/dementia-free adults from 13 population-based cohort studies within the Cohorts for Heart and Aging Research in Genomic Epidemiology consortium, among which 17 790 were of European ancestry and 2929 of African ancestry. We genotyped these participants at ≈250 000 mostly exonic variants with Illumina HumanExome BeadChip arrays. We performed ethnicity-specific linear regression on rank-normalized WMH in each study separately, which were then combined in meta-analyses to test for association with single variants and genes aggregating the effects of putatively functional low-frequency/rare variants. We then sought replication of the top findings in 1192 adults (European ancestry) with whole exome/genome sequencing data from 2 independent studies. RESULTS: At 17q25, we confirmed the association of multiple common variants in , , and (<6×10). We also identified a novel association with 2 low-frequency nonsynonymous variants in (lead, rs34136221; =4.5×10) partially independent of known common signal (=1.4×10). We further identified a locus at 2q33 containing common variants in , , and (lead, rs2351524; =1.9×10). Although our novel findings were not replicated because of limited power and possible differences in study design, meta-analysis of the discovery and replication samples yielded stronger association for the 2 low-frequency variants (=2.8×10). CONCLUSIONS: Both common and low-frequency/rare functional variants influence WMH. Larger replication and experimental follow-up are essential to confirm our findings and uncover the biological causal mechanisms of age-related WMH.

Exome-chip meta-analysis identifies novel loci associated with cardiac conduction, including ADAMTS6. - Prins, Bram P; Mead, Timothy J; Brody, Jennifer A; Sveinbjornsson, Gardar; Ntalla, Ioanna; Bihlmeyer, Nathan A; van den Berg, Marten; Bork-Jensen, Jette; Cappellani, Stefania; Van Duijvenboden, Stefan; Klena, Nikolai T; Gabriel, George C; et al. (Genome Biol, 2018)
BACKGROUND: Genome-wide association studies conducted on QRS duration, an electrocardiographic measurement associated with heart failure and sudden cardiac death, have led to novel biological insights into cardiac function. However, the variants identified fall predominantly in non-coding regions and their underlying mechanisms remain unclear. RESULTS: Here, we identify putative functional coding variation associated with changes in the QRS interval duration by combining Illumina HumanExome BeadChip genotype data from 77,898 participants of European ancestry and 7695 of African descent in our discovery cohort, followed by replication in 111,874 individuals of European ancestry from the UK Biobank and deCODE cohorts. We identify ten novel loci, seven within coding regions, including ADAMTS6, significantly associated with QRS duration in gene-based analyses. ADAMTS6 encodes a secreted metalloprotease of currently unknown function. In vitro validation analysis shows that the QRS-associated variants lead to impaired ADAMTS6 secretion and loss-of function analysis in mice demonstrates a previously unappreciated role for ADAMTS6 in connexin 43 gap junction expression, which is essential for myocardial conduction. CONCLUSIONS: Our approach identifies novel coding and non-coding variants underlying ventricular depolarization and provides a possible mechanism for the ADAMTS6-associated conduction changes.

ExomeChip-Wide Analysis of 95 626 Individuals Identifies 10 Novel Loci Associated With QT and JT Intervals. - Bihlmeyer, Nathan A; Brody, Jennifer A; Smith, Albert Vernon; Warren, Helen R; Lin, Honghuang; Isaacs, Aaron; Liu, Ching-Ti; Marten, Jonathan; Radmanesh, Farid; Hall, Leanne M; Grarup, Niels; Mei, Hao; et al. (Circ Genom Precis Med, 2018)
BACKGROUND: QT interval, measured through a standard ECG, captures the time it takes for the cardiac ventricles to depolarize and repolarize. JT interval is the component of the QT interval that reflects ventricular repolarization alone. Prolonged QT interval has been linked to higher risk of sudden cardiac arrest. METHODS AND RESULTS: We performed an ExomeChip-wide analysis for both QT and JT intervals, including 209 449 variants, both common and rare, in 17 341 genes from the Illumina Infinium HumanExome BeadChip. We identified 10 loci that modulate QT and JT interval duration that have not been previously reported in the literature using single-variant statistical models in a meta-analysis of 95 626 individuals from 23 cohorts (comprised 83 884 European ancestry individuals, 9610 blacks, 1382 Hispanics, and 750 Asians). This brings the total number of ventricular repolarization associated loci to 45. In addition, our approach of using coding variants has highlighted the role of 17 specific genes for involvement in ventricular repolarization, 7 of which are in novel loci. CONCLUSIONS: Our analyses show a role for myocyte internal structure and interconnections in modulating QT interval duration, adding to previous known roles of potassium, sodium, and calcium ion regulation, as well as autonomic control. We anticipate that these discoveries will open new paths to the goal of making novel remedies for the prevention of lethal ventricular arrhythmias and sudden cardiac arrest.

Fatty acid biomarkers of dairy fat consumption and incidence of type 2 diabetes: A pooled analysis of prospective cohort studies. - Imamura, Fumiaki; Fretts, Amanda; Marklund, Matti; Ardisson Korat, Andres V; Yang, Wei-Sin; Lankinen, Maria; Qureshi, Waqas; Helmer, Catherine; Chen, Tzu-An; Wong, Kerry; Bassett, Julie K; Murphy, Rachel; et al. (PLoS Med, 2018)
BACKGROUND: We aimed to investigate prospective associations of circulating or adipose tissue odd-chain fatty acids 15:0 and 17:0 and trans-palmitoleic acid, t16:1n-7, as potential biomarkers of dairy fat intake, with incident type 2 diabetes (T2D). METHODS AND FINDINGS: Sixteen prospective cohorts from 12 countries (7 from the United States, 7 from Europe, 1 from Australia, 1 from Taiwan) performed new harmonised individual-level analysis for the prospective associations according to a standardised plan. In total, 63,682 participants with a broad range of baseline ages and BMIs and 15,180 incident cases of T2D over the average of 9 years of follow-up were evaluated. Study-specific results were pooled using inverse-variance-weighted meta-analysis. Prespecified interactions by age, sex, BMI, and race/ethnicity were explored in each cohort and were meta-analysed. Potential heterogeneity by cohort-specific characteristics (regions, lipid compartments used for fatty acid assays) was assessed with metaregression. After adjustment for potential confounders, including measures of adiposity (BMI, waist circumference) and lipogenesis (levels of palmitate, triglycerides), higher levels of 15:0, 17:0, and t16:1n-7 were associated with lower incidence of T2D. In the most adjusted model, the hazard ratio (95% CI) for incident T2D per cohort-specific 10th to 90th percentile range of 15:0 was 0.80 (0.73-0.87); of 17:0, 0.65 (0.59-0.72); of t16:1n7, 0.82 (0.70-0.96); and of their sum, 0.71 (0.63-0.79). In exploratory analyses, similar associations for 15:0, 17:0, and the sum of all three fatty acids were present in both genders but stronger in women than in men (pinteraction < 0.001). Whereas studying associations with biomarkers has several advantages, as limitations, the biomarkers do not distinguish between different food sources of dairy fat (e.g., cheese, yogurt, milk), and residual confounding by unmeasured or imprecisely measured confounders may exist. CONCLUSIONS: In a large meta-analysis that pooled the findings from 16 prospective cohort studies, higher levels of 15:0, 17:0, and t16:1n-7 were associated with a lower risk of T2D.
Keywords: Aged; Australia; Biomarkers; Dairy Products; Diabetes Mellitus, Type 2; Dietary Fats; Europe; Fatty Acids; Fatty Acids, Monounsaturated; Female; Humans; Incidence; Male; Middle Aged; Prospective Studies; Sex Factors; Taiwan; United States

Generalization and fine mapping of red blood cell trait genetic associations to multi-ethnic populations: The PAGE Study. - Jo Hodonsky, Chani; Schurmann, Claudia; Schick, Ursula M; Kocarnik, Jonathan; Tao, Ran; van Rooij, Frank Ja; Wassel, Christina; Buyske, Steve; Fornage, Myriam; Hindorff, Lucia A; Floyd, James S; Ganesh, Santhi K; et al. (Am J Hematol, 2018)
Red blood cell (RBC) traits provide insight into a wide range of physiological states and exhibit moderate to high heritability, making them excellent candidates for genetic studies to inform underlying biologic mechanisms. Previous RBC trait genome-wide association studies were performed primarily in European- or Asian-ancestry populations, missing opportunities to inform understanding of RBC genetic architecture in diverse populations and reduce intervals surrounding putative functional SNPs through fine-mapping. Here, we report the first fine-mapping of six correlated (Pearson's r range: |0.04 - 0.92|) RBC traits in up to 19,036 African Americans and 19,562 Hispanic/Latinos participants of the Population Architecture using Genomics and Epidemiology (PAGE) consortium. Trans-ethnic meta-analysis of race/ethnic- and study-specific estimates for approximately 11,000 SNPs flanking 13 previously identified association signals as well as 150,000 additional array-wide SNPs was performed using inverse-variance meta-analysis after adjusting for study and clinical covariates. Approximately half of previously reported index SNP-RBC trait associations generalized to the trans-ethnic study population (p<1.7x10 ); previously unreported independent association signals within the ABO region reinforce the potential for multiple functional variants affecting the same locus. Trans-ethnic fine-mapping did not reveal additional signals at the HFE locus independent of the known functional variants. Finally, we identified a potential novel association in the Hispanic/Latino study population at the HECTD4/RPL6 locus for RBC count (p=1.9x10 ). The identification of a previously unknown association, generalization of a large proportion of known association signals, and refinement of known association signals all exemplify the benefits of genetic studies in diverse populations. This article is protected by copyright. All rights reserved.

Genetic analysis of over 1 million people identifies 535 new loci associated with blood pressure traits. - Evangelou, Evangelos; Warren, Helen R; Mosen-Ansorena, David; Mifsud, Borbala; Pazoki, Raha; Gao, He; Ntritsos, Georgios; Dimou, Niki; Cabrera, Claudia P; Karaman, Ibrahim; Ng, Fu Liang; Evangelou, Marina; et al. (Nat Genet, 2018)
High blood pressure is a highly heritable and modifiable risk factor for cardiovascular disease. We report the largest genetic association study of blood pressure traits (systolic, diastolic and pulse pressure) to date in over 1 million people of European ancestry. We identify 535 novel blood pressure loci that not only offer new biological insights into blood pressure regulation but also highlight shared genetic architecture between blood pressure and lifestyle exposures. Our findings identify new biological pathways for blood pressure regulation with potential for improved cardiovascular disease prevention in the future.

Genetic Variants Associated with Circulating Fibroblast Growth Factor 23. - Robinson-Cohen, Cassianne; Bartz, Traci M; Lai, Dongbing; Ikizler, T Alp; Peacock, Munro; Imel, Erik A; Michos, Erin D; Foroud, Tatiana M; Åkesson, Kristina; Taylor, Kent D; Malmgren, Linnea; Matsushita, Kunihiro; et al. (J Am Soc Nephrol, 2018)
BACKGROUND: Fibroblast growth factor 23 (FGF23), a bone-derived hormone that regulates phosphorus and vitamin D metabolism, contributes to the pathogenesis of mineral and bone disorders in CKD and is an emerging cardiovascular risk factor. Central elements of FGF23 regulation remain incompletely understood; genetic variation may help explain interindividual differences. METHODS: We performed a meta-analysis of genome-wide association studies of circulating FGF23 concentrations among 16,624 participants of European ancestry from seven cohort studies, excluding participants with eGFR<30 ml/min per 1.73 m to focus on FGF23 under normal conditions. We evaluated the association of single-nucleotide polymorphisms (SNPs) with natural log-transformed FGF23 concentration, adjusted for age, sex, study site, and principal components of ancestry. A second model additionally adjusted for BMI and eGFR. RESULTS: We discovered 154 SNPs from five independent regions associated with FGF23 concentration. The SNP with the strongest association, rs17216707 (=3.0×10), lies upstream of , which encodes the primary catabolic enzyme for 1,25-dihydroxyvitamin D and 25-hydroxyvitamin D. Each additional copy of the T allele at this locus is associated with 5% higher FGF23 concentration. Another locus strongly associated with variations in FGF23 concentration is rs11741640, within and upstream of (a gene involved in renal phosphate transport). Additional adjustment for BMI and eGFR did not materially alter the magnitude of these associations. Another top locus (within , the ABO blood group transferase gene) was no longer statistically significant at the genome-wide level. CONCLUSIONS: Common genetic variants located near genes involved in vitamin D metabolism and renal phosphate transport are associated with differences in circulating FGF23 concentrations.

Genetic Variation in Genes Underlying Diverse Dementias May Explain a Small Proportion of Cases in the Alzheimer's Disease Sequencing Project. - Blue, Elizabeth E; Bis, Joshua C; Dorschner, Michael O; Tsuang, Debby W; Barral, Sandra M; Beecham, Gary; Below, Jennifer E; Bush, William S; Butkiewicz, Mariusz; Cruchaga, Carlos; DeStefano, Anita; Farrer, Lindsay A; et al. (Dement Geriatr Cogn Disord, 2018)
BACKGROUND/AIMS: The Alzheimer's Disease Sequencing Project (ADSP) aims to identify novel genes influencing Alzheimer's disease (AD). Variants within genes known to cause dementias other than AD have previously been associated with AD risk. We describe evidence of co-segregation and associations between variants in dementia genes and clinically diagnosed AD within the ADSP. METHODS: We summarize the properties of known pathogenic variants within dementia genes, describe the co-segregation of variants annotated as "pathogenic" in ClinVar and new candidates observed in ADSP families, and test for associations between rare variants in dementia genes in the ADSP case-control study. The participants were clinically evaluated for AD, and they represent European, Caribbean Hispanic, and isolate Dutch populations. RESULTS/CONCLUSIONS: Pathogenic variants in dementia genes were predominantly rare and conserved coding changes. Pathogenic variants within ARSA, CSF1R, and GRN were observed, and candidate variants in GRN and CHMP2B were nominated in ADSP families. An independent case-control study provided evidence of an association between variants in TREM2, APOE, ARSA, CSF1R, PSEN1, and MAPT and risk of AD. Variants in genes which cause dementing disorders may influence the clinical diagnosis of AD in a small proportion of cases within the ADSP.

Genome Analyses of >200,000 Individuals Identify 58 Loci for Chronic Inflammation and Highlight Pathways that Link Inflammation and Complex Disorders. - Ligthart, Symen; Vaez, Ahmad; Võsa, Urmo; Stathopoulou, Maria G; de Vries, Paul S; Prins, Bram P; van der Most, Peter J; Tanaka, Toshiko; Naderi, Elnaz; Rose, Lynda M; Wu, Ying; Karlsson, Robert; et al. (Am J Hum Genet, 2018)
C-reactive protein (CRP) is a sensitive biomarker of chronic low-grade inflammation and is associated with multiple complex diseases. The genetic determinants of chronic inflammation remain largely unknown, and the causal role of CRP in several clinical outcomes is debated. We performed two genome-wide association studies (GWASs), on HapMap and 1000 Genomes imputed data, of circulating amounts of CRP by using data from 88 studies comprising 204,402 European individuals. Additionally, we performed in silico functional analyses and Mendelian randomization analyses with several clinical outcomes. The GWAS meta-analyses of CRP revealed 58 distinct genetic loci (p < 5 × 10). After adjustment for body mass index in the regression analysis, the associations at all except three loci remained. The lead variants at the distinct loci explained up to 7.0% of the variance in circulating amounts of CRP. We identified 66 gene sets that were organized in two substantially correlated clusters, one mainly composed of immune pathways and the other characterized by metabolic pathways in the liver. Mendelian randomization analyses revealed a causal protective effect of CRP on schizophrenia and a risk-increasing effect on bipolar disorder. Our findings provide further insights into the biology of inflammation and could lead to interventions for treating inflammation and its clinical consequences.

Genome-wide analyses identify a role for SLC17A4 and AADAT in thyroid hormone regulation. - Teumer, Alexander; Chaker, Layal; Groeneweg, Stefan; Li, Yong; Di Munno, Celia; Barbieri, Caterina; Schultheiss, Ulla T; Traglia, Michela; Ahluwalia, Tarunveer S; Akiyama, Masato; Appel, Emil Vincent R; Arking, Dan E; et al. (Nat Commun, 2018)
Thyroid dysfunction is an important public health problem, which affects 10% of the general population and increases the risk of cardiovascular morbidity and mortality. Many aspects of thyroid hormone regulation have only partly been elucidated, including its transport, metabolism, and genetic determinants. Here we report a large meta-analysis of genome-wide association studies for thyroid function and dysfunction, testing 8 million genetic variants in up to 72,167 individuals. One-hundred-and-nine independent genetic variants are associated with these traits. A genetic risk score, calculated to assess their combined effects on clinical end points, shows significant associations with increased risk of both overt (Graves' disease) and subclinical thyroid disease, as well as clinical complications. By functional follow-up on selected signals, we identify a novel thyroid hormone transporter (SLC17A4) and a metabolizing enzyme (AADAT). Together, these results provide new knowledge about thyroid hormone physiology and disease, opening new possibilities for therapeutic targets.

Genome-wide association meta-analysis of circulating odd-numbered chain saturated fatty acids: Results from the CHARGE Consortium. - de Oliveira Otto, Marcia C; Lemaitre, Rozenn N; Sun, Qi; King, Irena B; Wu, Jason H Y; Manichaikul, Ani; Rich, Stephen S; Tsai, Michael Y; Chen, Y D; Fornage, Myriam; Weihua, Guan; Aslibekyan, Stella; et al. (PLoS One, 2018)
BACKGROUND: Odd-numbered chain saturated fatty acids (OCSFA) have been associated with potential health benefits. Although some OCSFA (e.g., C15:0 and C17:0) are found in meats and dairy products, sources and metabolism of C19:0 and C23:0 are relatively unknown, and the influence of non-dietary determinants, including genetic factors, on circulating levels of OCSFA is not established. OBJECTIVE: To elucidate the biological processes that influence circulating levels of OCSFA by investigating associations between genetic variation and OCSFA. DESIGN: We performed a meta-analysis of genome-wide association studies (GWAS) of plasma phospholipid/erythrocyte levels of C15:0, C17:0, C19:0, and C23:0 among 11,494 individuals of European descent. We also investigated relationships between specific single nucleotide polymorphisms (SNPs) in the lactase (LCT) gene, associated with adult-onset lactase intolerance, with circulating levels of dairy-derived OCSFA, and evaluated associations of candidate sphingolipid genes with C23:0 levels. RESULTS: We found no genome-wide significant evidence that common genetic variation is associated with circulating levels of C15:0 or C23:0. In two cohorts with available data, we identified one intronic SNP (rs13361131) in myosin X gene (MYO10) associated with C17:0 level (P = 1.37×10-8), and two intronic SNP (rs12874278 and rs17363566) in deleted in lymphocytic leukemia 1 (DLEU1) region associated with C19:0 level (P = 7.07×10-9). In contrast, when using a candidate-gene approach, we found evidence that three SNPs in LCT (rs11884924, rs16832067, and rs3816088) are associated with circulating C17:0 level (adjusted P = 4×10-2). In addition, nine SNPs in the ceramide synthase 4 (CERS4) region were associated with circulating C23:0 levels (adjusted P<5×10-2). CONCLUSIONS: Our findings suggest that circulating levels of OCSFA may be predominantly influenced by non-genetic factors. SNPs associated with C17:0 level in the LCT gene may reflect genetic influence in dairy consumption or in metabolism of dairy foods. SNPs associated with C23:0 may reflect a role of genetic factors in the synthesis of sphingomyelin.
Keywords: Fatty Acids; Genome-Wide Association Study; Humans; Introns; Lactase; Myosins; Polymorphism, Single Nucleotide; Sphingomyelins; Sphingosine N-Acyltransferase; Tumor Suppressor Proteins

Genome-wide association study and meta-analysis identify loci associated with ventricular and supraventricular ectopy. - Napier, Melanie D; Franceschini, Nora; Gondalia, Rahul; Stewart, James D; Méndez-Giráldez, Rául; Sitlani, Colleen M; Seyerle, Amanda A; Highland, Heather M; Li, Yun; Wilhelmsen, Kirk C; Yan, Song; Duan, Qing; et al. (Sci Rep, 2018)
The genetic basis of supraventricular and ventricular ectopy (SVE, VE) remains largely uncharacterized, despite established genetic mechanisms of arrhythmogenesis. To identify novel genetic variants associated with SVE/VE in ancestrally diverse human populations, we conducted a genome-wide association study of electrocardiographically identified SVE and VE in five cohorts including approximately 43,000 participants of African, European and Hispanic/Latino ancestry. In thirteen ancestry-stratified subgroups, we tested multivariable-adjusted associations of SVE and VE with single nucleotide polymorphism (SNP) dosage. We combined subgroup-specific association estimates in inverse variance-weighted, fixed-effects and Bayesian meta-analyses. We also combined fixed-effects meta-analytic t-test statistics for SVE and VE in multi-trait SNP association analyses. No loci reached genome-wide significance in trans-ethnic meta-analyses. However, we found genome-wide significant SNPs intronic to an apoptosis-enhancing gene previously associated with QRS interval duration (FAF1; lead SNP rs7545860; effect allele frequency = 0.02; P = 2.0 × 10) in multi-trait analysis among European ancestry participants and near a locus encoding calcium-dependent glycoproteins (DSC3; lead SNP rs8086068; effect allele frequency = 0.17) in meta-analysis of SVE (P = 4.0 × 10) and multi-trait analysis (P = 2.9 × 10) among African ancestry participants. The novel findings suggest several mechanisms by which genetic variation may predispose to ectopy in humans and highlight the potential value of leveraging pleiotropy in future studies of ectopy-related phenotypes.

Genome-wide association study in 79,366 European-ancestry individuals informs the genetic architecture of 25-hydroxyvitamin D levels. - Jiang, Xia; O'Reilly, Paul F; Aschard, Hugues; Hsu, Yi-Hsiang; Richards, J Brent; Dupuis, Josée; Ingelsson, Erik; Karasik, David; Pilz, Stefan; Berry, Diane; Kestenbaum, Bryan; Zheng, Jusheng; et al. (Nat Commun, 2018)
Vitamin D is a steroid hormone precursor that is associated with a range of human traits and diseases. Previous GWAS of serum 25-hydroxyvitamin D concentrations have identified four genome-wide significant loci (GC, NADSYN1/DHCR7, CYP2R1, CYP24A1). In this study, we expand the previous SUNLIGHT Consortium GWAS discovery sample size from 16,125 to 79,366 (all European descent). This larger GWAS yields two additional loci harboring genome-wide significant variants (P = 4.7×10 at rs8018720 in SEC23A, and P = 1.9×10 at rs10745742 in AMDHD1). The overall estimate of heritability of 25-hydroxyvitamin D serum concentrations attributable to GWAS common SNPs is 7.5%, with statistically significant loci explaining 38% of this total. Further investigation identifies signal enrichment in immune and hematopoietic tissues, and clustering with autoimmune diseases in cell-type-specific analysis. Larger studies are required to identify additional common SNPs, and to explore the role of rare or structural variants and gene-gene interactions in the heritability of circulating 25-hydroxyvitamin D levels.

Genome-wide association study of 23,500 individuals identifies 7 loci associated with brain ventricular volume. - Vojinovic, Dina; Adams, Hieab H; Jian, Xueqiu; Yang, Qiong; Smith, Albert Vernon; Bis, Joshua C; Teumer, Alexander; Scholz, Markus; Armstrong, Nicola J; Hofer, Edith; Saba, Yasaman; Luciano, Michelle; et al. (Nat Commun, 2018)
The volume of the lateral ventricles (LV) increases with age and their abnormal enlargement is a key feature of several neurological and psychiatric diseases. Although lateral ventricular volume is heritable, a comprehensive investigation of its genetic determinants is lacking. In this meta-analysis of genome-wide association studies of 23,533 healthy middle-aged to elderly individuals from 26 population-based cohorts, we identify 7 genetic loci associated with LV volume. These loci map to chromosomes 3q28, 7p22.3, 10p12.31, 11q23.1, 12q23.3, 16q24.2, and 22q13.1 and implicate pathways related to tau pathology, S1P signaling, and cytoskeleton organization. We also report a significant genetic overlap between the thalamus and LV volumes (ρ = -0.59, p-value = 3.14 × 10), suggesting that these brain structures may share a common biology. These genetic associations of LV volume provide insights into brain morphology.

Genome-Wide Association Trans-Ethnic Meta-Analyses Identifies Novel Associations Regulating Coagulation Factor VIII and von Willebrand Factor Plasma Levels. - Sabater-Lleal, Maria; Huffman, Jennifer E; de Vries, Paul S; Marten, Jonathan; Mastrangelo, Michael A; Song, Ci; Pankratz, Nathan; Ward-Caviness, Cavin K; Yanek, Lisa R; Trompet, Stella; Delgado, Graciela E; Guo, Xiuqing; et al. (Circulation, 2018)
BACKGROUND: Factor VIII (FVIII) and its carrier protein von Willebrand factor (VWF) are associated with risk of arterial and venous thrombosis and with hemorrhagic disorders. We aimed to identify and functionally test novel genetic associations regulating plasma FVIII and VWF. METHODS: We meta-analyzed genome-wide association results from 46,354 individuals of European, African, East Asian, and Hispanic ancestry. All studies performed linear regression analysis using an additive genetic model and associated approximately 35 million imputed variants with natural-log transformed phenotype levels. In vitro gene silencing in cultured endothelial cells was performed for candidate genes to provide additional evidence on association and function. Two-sample Mendelian randomization (MR) analyses were applied to test the causal role of FVIII and VWF plasma levels on the risk of arterial and venous thrombotic events. RESULTS: We identified 13 novel genome-wide significant (p≤2.5x10) associations; 7 with FVIII levels ( FCHO2/TMEM171/TNPO1, HLA, SOX17/RP1, LINC00583/NFIB, RAB5C-KAT2A, RPL3/TAB1/SYNGR1, and ARSA) and 11 with VWF levels ( PDHB/PXK/KCTD6, SLC39A8, FCHO2/TMEM171/TNPO1, HLA, GIMAP7/GIMAP4, OR13C5/NIPSNAP, DAB2IP, C2CD4B, RAB5C-KAT2A, TAB1/SYNGR1, and ARSA), beyond 10 previously reported associations with these phenotypes. Functional validation provided further evidence of association for all loci on VWF except ARSA and DAB2IP. MR suggested causal effects of plasma FVIII activity levels on venous thrombosis and coronary artery disease risk and plasma VWF levels on ischemic stroke risk. CONCLUSIONS: The meta-analysis identified 13 novel genetic loci regulating FVIII and VWF plasma levels, 10 of which we validated functionally. We provide some evidence for a causal role of these proteins in thrombotic events.

Genome-Wide Associations of Global Electrical Heterogeneity ECG Phenotype: The ARIC (Atherosclerosis Risk in Communities) Study and CHS (Cardiovascular Health Study). - Tereshchenko, Larisa G; Sotoodehnia, Nona; Sitlani, Colleen M; Ashar, Foram N; Kabir, Muammar; Biggs, Mary L; Morley, Michael P; Waks, Jonathan W; Soliman, Elsayed Z; Buxton, Alfred E; Biering-Sørensen, Tor; Solomon, Scott D; et al. (J Am Heart Assoc, 2018)
BACKGROUND: ECG global electrical heterogeneity (GEH) is associated with sudden cardiac death. We hypothesized that a genome-wide association study would identify genetic loci related to GEH. METHODS AND RESULTS: We tested genotyped and imputed variants in black (N=3057) and white (N=10 769) participants in the ARIC (Atherosclerosis Risk in Communities) study and CHS (Cardiovascular Health Study). GEH (QRS-T angle, sum absolute QRST integral, spatial ventricular gradient magnitude, elevation, azimuth) was measured on 12-lead ECGs. Linear regression models were constructed with each GEH variable as an outcome, adjusted for age, sex, height, body mass index, study site, and principal components to account for ancestry. GWAS identified 10 loci that showed genome-wide significant association with GEH in whites or joint ancestry. The strongest signal (rs7301677, near ) was associated with QRS-T angle (white standardized β+0.16 [95% CI 0.13-0.19]; =1.5×10), spatial ventricular gradient elevation (+0.11 [0.08-0.14]; =2.1×10), and spatial ventricular gradient magnitude (-0.12 [95% CI -0.15 to -0.09]; =5.9×10). Altogether, GEH-SNPs explained 1.1% to 1.6% of GEH variance. Loci on chromosomes 4 (near ), 5 (), 11 (11p11.2 region cluster), and 7 (near ) are novel ECG phenotype-associated loci. Several loci significantly associated with gene expression in the left ventricle ( locus-with ; locus-with ), and atria ( locus-with expression of a long non-coding RNA and ). CONCLUSIONS: We identified 10 genetic loci associated with ECG GEH. Replication of GEH GWAS findings in independent cohorts is warranted. Further studies of GEH-loci may uncover mechanisms of arrhythmogenic remodeling in response to cardiovascular risk factors.

Genome-wide meta-analysis of 158,000 individuals of European ancestry identifies three loci associated with chronic back pain. - Suri, Pradeep; Palmer, Melody R; Tsepilov, Yakov A; Freidin, Maxim B; Boer, Cindy G; Yau, Michelle S; Evans, Daniel S; Gelemanovic, Andrea; Bartz, Traci M; Nethander, Maria; Arbeeva, Liubov; Karssen, Lennart; et al. (PLoS Genet, 2018)
Back pain is the #1 cause of years lived with disability worldwide, yet surprisingly little is known regarding the biology underlying this symptom. We conducted a genome-wide association study (GWAS) meta-analysis of chronic back pain (CBP). Adults of European ancestry were included from 15 cohorts in the Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) consortium, and from the UK Biobank interim data release. CBP cases were defined as those reporting back pain present for ≥3-6 months; non-cases were included as comparisons ("controls"). Each cohort conducted genotyping using commercially available arrays followed by imputation. GWAS used logistic regression models with additive genetic effects, adjusting for age, sex, study-specific covariates, and population substructure. The threshold for genome-wide significance in the fixed-effect inverse-variance weighted meta-analysis was p<5×10-8. Suggestive (p<5×10-7) and genome-wide significant (p<5×10-8) variants were carried forward for replication or further investigation in the remaining UK Biobank participants not included in the discovery sample. The discovery sample comprised 158,025 individuals, including 29,531 CBP cases. A genome-wide significant association was found for the intronic variant rs12310519 in SOX5 (OR 1.08, p = 7.2×10-10). This was subsequently replicated in 283,752 UK Biobank participants not included in the discovery sample, including 50,915 cases (OR 1.06, p = 5.3×10-11), and exceeded genome-wide significance in joint meta-analysis (OR 1.07, p = 4.5×10-19). We found suggestive associations at three other loci in the discovery sample, two of which exceeded genome-wide significance in joint meta-analysis: an intergenic variant, rs7833174, located between CCDC26 and GSDMC (OR 1.05, p = 4.4×10-13), and an intronic variant, rs4384683, in DCC (OR 0.97, p = 2.4×10-10). In this first reported meta-analysis of GWAS for CBP, we identified and replicated a genetic locus associated with CBP (SOX5). We also identified 2 other loci that reached genome-wide significance in a 2-stage joint meta-analysis (CCDC26/GSDMC and DCC).

Genome-wide meta-analysis of SNP-by9-ACEI/ARB and SNP-by-thiazide diuretic and effect on serum potassium in cohorts of European and African ancestry. - Irvin, Marguerite R; Sitlani, Colleen M; Noordam, Raymond; Avery, Christie L; Bis, Joshua C; Floyd, James S; Li, Jin; Limdi, Nita A; Srinivasasainagendra, Vinodh; Stewart, James; de Mutsert, Renée; Mook-Kanamori, Dennis O; et al. (Pharmacogenomics J, 2018)
We evaluated interactions of SNP-by-ACE-I/ARB and SNP-by-TD on serum potassium (K+) among users of antihypertensive treatments (anti-HTN). Our study included seven European-ancestry (EA) (N = 4835) and four African-ancestry (AA) cohorts (N = 2016). We performed race-stratified, fixed-effect, inverse-variance-weighted meta-analyses of 2.5 million SNP-by-drug interaction estimates; race-combined meta-analysis; and trans-ethnic fine-mapping. Among EAs, we identified 11 significant SNPs (P < 5 × 10) for SNP-ACE-I/ARB interactions on serum K+ that were located between NR2F1-AS1 and ARRDC3-AS1 on chromosome 5 (top SNP rs6878413 P = 1.7 × 10; ratio of serum K+ in ACE-I/ARB exposed compared to unexposed is 1.0476, 1.0280, 1.0088 for the TT, AT, and AA genotypes, respectively). Trans-ethnic fine mapping identified the same group of SNPs on chromosome 5 as genome-wide significant for the ACE-I/ARB analysis. In conclusion, SNP-by-ACE-I /ARB interaction analyses uncovered loci that, if replicated, could have future implications for the prevention of arrhythmias due to anti-HTN treatment-related hyperkalemia. Before these loci can be identified as clinically relevant, future validation studies of equal or greater size in comparison to our discovery effort are needed.

GWAS and colocalization analyses implicate carotid intima-media thickness and carotid plaque loci in cardiovascular outcomes. - Franceschini, Nora; Giambartolomei, Claudia; de Vries, Paul S; Finan, Chris; Bis, Joshua C; Huntley, Rachael P; Lovering, Ruth C; Tajuddin, Salman M; Winkler, Thomas W; Graff, Misa; Kavousi, Maryam; Dale, Caroline; et al. (Nat Commun, 2018)
Carotid artery intima media thickness (cIMT) and carotid plaque are measures of subclinical atherosclerosis associated with ischemic stroke and coronary heart disease (CHD). Here, we undertake meta-analyses of genome-wide association studies (GWAS) in 71,128 individuals for cIMT, and 48,434 individuals for carotid plaque traits. We identify eight novel susceptibility loci for cIMT, one independent association at the previously-identified PINX1 locus, and one novel locus for carotid plaque. Colocalization analysis with nearby vascular expression quantitative loci (cis-eQTLs) derived from arterial wall and metabolic tissues obtained from patients with CHD identifies candidate genes at two potentially additional loci, ADAMTS9 and LOXL4. LD score regression reveals significant genetic correlations between cIMT and plaque traits, and both cIMT and plaque with CHD, any stroke subtype and ischemic stroke. Our study provides insights into genes and tissue-specific regulatory mechanisms linking atherosclerosis both to its functional genomic origins and its clinical consequences in humans.
Keywords: ADAMTS9 Protein; Amino Acid Oxidoreductases; Carotid Intima-Media Thickness; Coronary Disease; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Lod Score; Plaque, Atherosclerotic; Polymorphism, Single Nucleotide; Quantitative Trait Loci; Risk Factors

Harmonization of Respiratory Data From 9 US Population-Based Cohorts: The NHLBI Pooled Cohorts Study. - Oelsner, Elizabeth C; Balte, Pallavi P; Cassano, Patricia A; Couper, David; Enright, Paul L; Folsom, Aaron R; Hankinson, John; Jacobs, David R; Kalhan, Ravi; Kaplan, Robert; Kronmal, Richard; Lange, Leslie; et al. (Am J Epidemiol, 2018)
Chronic lower respiratory diseases (CLRDs) are the fourth leading cause of death in the United States. To support investigations into CLRD risk determinants and new approaches to primary prevention, we aimed to harmonize and pool respiratory data from US general population-based cohorts. Data were obtained from prospective cohorts that performed prebronchodilator spirometry and were harmonized following 2005 ATS/ERS standards. In cohorts conducting follow-up for noncardiovascular events, CLRD events were defined as hospitalizations/deaths adjudicated as CLRD-related or assigned relevant administrative codes. Coding and variable names were applied uniformly. The pooled sample included 65,251 adults in 9 cohorts followed-up for CLRD-related mortality over 653,380 person-years during 1983-2016. Average baseline age was 52 years; 56% were female; 49% were never-smokers; and racial/ethnic composition was 44% white, 22% black, 28% Hispanic/Latino, and 5% American Indian. Over 96% had complete data on smoking, clinical CLRD diagnoses, and dyspnea. After excluding invalid spirometry examinations (13%), there were 105,696 valid examinations (median, 2 per participant). Of 29,351 participants followed for CLRD hospitalizations, median follow-up was 14 years; only 5% were lost to follow-up at 10 years. The NHLBI Pooled Cohorts Study provides a harmonization standard applied to a large, US population-based sample that may be used to advance epidemiologic research on CLRD.

Hospital and clinical care costs associated with atrial fibrillation for Medicare beneficiaries in the Cardiovascular Health Study and the Framingham Heart Study. - Delaney, Joseph Ac; Yin, Xiaoyan; Fontes, João Daniel; Wallace, Erin R; Skinner, Asheley; Wang, Na; Hammill, Bradley G; Benjamin, Emelia J; Curtis, Lesley H; Heckbert, Susan R (SAGE Open Med, 2018)
Background: Atrial fibrillation is increasingly prevalent as the US population ages and is associated with significant morbidity and mortality. Care for patients with atrial fibrillation can be costly, US health care costs are comparatively high, and there are few cost estimates available that incorporate detailed measurement of comorbidities and their effects on costs. Methods and Results: In the Cardiovascular Health Study and the Framingham Heart Study, participants aged 65 years or older with newly diagnosed atrial fibrillation were matched on age and follow-up time to referents free of atrial fibrillation. The total clinical and hospital medical costs paid by Medicare Parts A and B (drug costs from Medicare Part D costs were not included) in the year prior to diagnosis (or matching) were compared with costs in the following year. Estimates were adjusted for other medical conditions and adjusted to 2009 dollars. In the Cardiovascular Health Study, 513 participants were diagnosed with new-onset atrial fibrillation and survived 30 days post-atrial fibrillation diagnosis, and 513 referents (as a control cohort) were identified, with a mean age of 77 years. In the Framingham Heart Study, we identified 336 participants diagnosed with atrial fibrillation, who survived 30 days post-atrial fibrillation diagnosis and matched these participants to 336 referents. We compared these new-onset atrial fibrillation participants with referents, using a difference in difference design to account for both time trends and differences between the two groups. The adjusted incremental cost for participants with atrial fibrillation, compared with referents, was US$18,060 (95% confidence interval: US$14,965-US$21,155) in the Cardiovascular Health Study and US$20,012 (95% confidence interval: US$15,057-US$24,966) in the Framingham Heart Study. The pooled estimate was US$18,601 (95% confidence interval: US$15,981-US$21,234). Conclusion: Atrial fibrillation was associated with increased costs in the year after diagnosis in two community-based cohorts, even after careful accounting for age, time period, and systematically measured comorbidities.

Impact of lung-function measures on cardiovascular disease events in older adults with metabolic syndrome and diabetes. - Lee, Hwa Mu; Zhao, Yanglu; Liu, Michael A; Yanez, David; Carnethon, Mercedes; Graham Barr, R; Wong, Nathan D (Clin Cardiol, 2018)
BACKGROUND: Individuals with metabolic syndrome (MetS) and diabetes (DM) are more likely to have decreased lung function and are at greater risk of cardiovascular disease (CVD). HYPOTHESIS: Lung-function measures can predict CVD events in older persons with MetS, DM, and neither condition. METHODS: We followed 4114 participants age ≥ 65 years with and without MetS or DM in the Cardiovascular Health Study. Cox regression examined the association of forced vital capacity (FVC) and 1-second forced expiratory volume (FEV ; percent of predicted values) with incident coronary heart disease and CVD events over 12.9 years. RESULTS: DM was present in 537 (13.1%) and MetS in 1277 (31.0%) participants. Comparing fourth vs first quartiles for FVC, risk of CVD events was 16% (HR: 0.84, 95% CI: 0.59-1.18), 23% (HR: 0.77, 95% CI: 0.60-0.99), and 30% (HR: 0.70, 95% CI: 0.58-0.84) lower in DM, MetS, and neither disease groups, respectively. For FEV , CVD risk was lower by 2% (HR: 0.98, 95% CI: 0.70-1.37), 26% (HR: 0.74, 95% CI: 0.59-0.93), and 31% (HR: 0.69, 95% CI: 0.57-0.82) in DM. Findings were strongest for predicting congestive heart failure (CHF) in all disease groups. C-statistics increased significantly with addition of FEV or FVC over risk factors for CVD and CHF among those with neither MetS nor DM. CONCLUSIONS: FEV and FVC are inversely related to CVD in older adults with and without MetS, but not DM (except for CHF); however, their value in incremental risk prediction beyond standard risk factors is limited mainly to metabolically healthier persons.

A Large-Scale Multi-ancestry Genome-wide Study Accounting for Smoking Behavior Identifies Multiple Significant Loci for Blood Pressure. - Sung, Yun J; Winkler, Thomas W; de Las Fuentes, Lisa; Bentley, Amy R; Brown, Michael R; Kraja, Aldi T; Schwander, Karen; Ntalla, Ioanna; Guo, Xiuqing; Franceschini, Nora; Lu, Yingchang; Cheng, Ching-Yu; et al. (Am J Hum Genet, 2018)
Genome-wide association analysis advanced understanding of blood pressure (BP), a major risk factor for vascular conditions such as coronary heart disease and stroke. Accounting for smoking behavior may help identify BP loci and extend our knowledge of its genetic architecture. We performed genome-wide association meta-analyses of systolic and diastolic BP incorporating gene-smoking interactions in 610,091 individuals. Stage 1 analysis examined ∼18.8 million SNPs and small insertion/deletion variants in 129,913 individuals from four ancestries (European, African, Asian, and Hispanic) with follow-up analysis of promising variants in 480,178 additional individuals from five ancestries. We identified 15 loci that were genome-wide significant (p < 5 × 10) in stage 1 and formally replicated in stage 2. A combined stage 1 and 2 meta-analysis identified 66 additional genome-wide significant loci (13, 35, and 18 loci in European, African, and trans-ancestry, respectively). A total of 56 known BP loci were also identified by our results (p < 5 × 10). Of the newly identified loci, ten showed significant interaction with smoking status, but none of them were replicated in stage 2. Several loci were identified in African ancestry, highlighting the importance of genetic studies in diverse populations. The identified loci show strong evidence for regulatory features and support shared pathophysiology with cardiometabolic and addiction traits. They also highlight a role in BP regulation for biological candidates such as modulators of vascular structure and function (CDKN1B, BCAR1-CFDP1, PXDN, EEA1), ciliopathies (SDCCAG8, RPGRIP1L), telomere maintenance (TNKS, PINX1, AKTIP), and central dopaminergic signaling (MSRA, EBF2).

Large-scale whole-exome sequencing association studies identify rare functional variants influencing serum urate levels. - Tin, Adrienne; Li, Yong; Brody, Jennifer A; Nutile, Teresa; Chu, Audrey Y; Huffman, Jennifer E; Yang, Qiong; Chen, Ming-Huei; Robinson-Cohen, Cassianne; Mace, Aurelien; Liu, Jun; Demirkan, Ayse; et al. (Nat Commun, 2018)
Elevated serum urate levels can cause gout, an excruciating disease with suboptimal treatment. Previous GWAS identified common variants with modest effects on serum urate. Here we report large-scale whole-exome sequencing association studies of serum urate and kidney function among ≤19,517 European ancestry and African-American individuals. We identify aggregate associations of low-frequency damaging variants in the urate transporters SLC22A12 (URAT1; p = 1.3 × 10) and SLC2A9 (p = 4.5 × 10). Gout risk in rare SLC22A12 variant carriers is halved (OR = 0.5, p = 4.9 × 10). Selected rare variants in SLC22A12 are validated in transport studies, confirming three as loss-of-function (R325W, R405C, and T467M) and illustrating the therapeutic potential of the new URAT1-blocker lesinurad. In SLC2A9, mapping of rare variants of large effects onto the predicted protein structure reveals new residues that may affect urate binding. These findings provide new insights into the genetic architecture of serum urate, and highlight molecular targets in SLC22A12 and SLC2A9 for lowering serum urate and preventing gout.
Keywords: Exome; Genetic Predisposition to Disease; Glucose Transport Proteins, Facilitative; Humans; Kidney Function Tests; Meta-Analysis as Topic; Organic Anion Transporters; Organic Cation Transport Proteins; Protein Structure, Secondary; Uric Acid

Leukoaraiosis is independently associated with naming outcome in poststroke aphasia. - Wright, Amy; Tippett, Donna; Saxena, Sadhvi; Sebastian, Rajani; Breining, Bonnie; Faria, Andreia; Hillis, Argye E (Neurology, 2018)
OBJECTIVE: To test the hypothesis that severity of leukoaraiosis in the noninfarcted hemisphere at onset is associated with poorer language outcome after poststroke aphasia independently of volume of infarct, damage to 3 critical language areas (left inferior frontal gyrus, superior longitudinal fasciculus, and superior temporal gyrus), comorbid conditions, and time since stroke. METHODS: In this cross-sectional study, we evaluated naming outcome (>3 months after stroke) in 42 individuals who initially had aphasia after stroke. We rated leukoaraiosis in the right hemisphere 1 to 4 weeks from onset of stroke using the Cardiovascular Health Study rating scale. We evaluated associations between severity of leukoaraiosis and each measure of naming using Spearman correlations and evaluated the independent contributions of leukoaraiosis, lesion volume, months since onset, comorbid conditions, and damage to critical nodes of the language network on language outcomes using logistic regression. We also evaluated associations between dichotomously defined leukoaraiosis and language outcomes using χ tests. RESULTS: Severity of leukoaraiosis at onset correlated with object naming (ρ = -0.56, = 0.0008) and word fluency (ρ = -0.37, = 0.01) outcomes. Severe leukoaraiosis was associated with failure to achieve the highest quartile of object naming and word fluency. Severity of leukoaraiosis was associated with degree of naming outcome with the use of both measures after controlling for lesion volume, months since stroke, comorbid conditions, and damage to specific locations. CONCLUSION: Naming outcome after poststroke aphasia is influenced by the initial severity of right hemisphere leukoaraiosis independently of other variables. Degree of recovery from aphasia may depend on the integrity of the noninfarcted brain tissue.

{Life-Course Genome-wide Association Study Meta-analysis of Total Body BMD and Assessment of Age-Specific Effects - Medina-Gomez, C.; Kemp, J. P.; Trajanoska, K.; Luan, J.; Chesi, A.; Ahluwalia, T. S.; Mook-Kanamori, D. O.; Ham, A.; Hartwig, F. P.; Evans, D. S.; Joro, R.; Nedeljkovic, I.; et al. (Am J Hum Genet, 2018)
Bone mineral density (BMD) assessed by DXA is used to evaluate bone health. In children, total body (TB) measurements are commonly used; in older individuals, BMD at the lumbar spine (LS) and femoral neck (FN) is used to diagnose osteoporosis. To date, genetic variants in more than 60 loci have been identified as associated with BMD. To investigate the genetic determinants of TB-BMD variation along the life course and test for age-specific effects, we performed a meta-analysis of 30 genome-wide association studies (GWASs) of TB-BMD including 66,628 individuals overall and divided across five age strata, each spanning 15 years. We identified variants associated with TB-BMD at 80 loci, of which 36 have not been previously identified; overall, they explain approximately 10% of the TB-BMD variance when combining all age groups and influence the risk of fracture. Pathway and enrichment analysis of the association signals showed clustering within gene sets implicated in the regulation of cell growth and SMAD proteins, overexpressed in the musculoskeletal system, and enriched in enhancer and promoter regions. These findings reveal TB-BMD as a relevant trait for genetic studies of osteoporosis, enabling the identification of variants and pathways influencing different bone compartments. Only variants in ESR1 and close proximity to RANKL showed a clear effect dependency on age. This most likely indicates that the majority of genetic variants identified influence BMD early in life and that their effect can be captured throughout the life course.

Low thyroid function is not associated with an accelerated deterioration in renal function. - Meuwese, Christiaan L; van Diepen, Merel; Cappola, Anne R; Sarnak, Mark J; Shlipak, Michael G; Bauer, Douglas C; Fried, Linda P; Iacoviello, Massimo; Vaes, Bert; Degryse, Jean; Khaw, Kay-Tee; Luben, Robert N; et al. (Nephrol Dial Transplant, 2018)
Background: Chronic kidney disease (CKD) is frequently accompanied by thyroid hormone dysfunction. It is currently unclear whether these alterations are the cause or consequence of CKD. This study aimed at studying the effect of thyroid hormone alterations on renal function in cross-sectional and longitudinal analyses in individuals from all adult age groups. Methods: Individual participant data (IPD) from 16 independent cohorts having measured thyroid stimulating hormone, free thyroxine levels and creatinine levels were included. Thyroid hormone status was defined using clinical cut-off values. Estimated glomerular filtration rates (eGFR) were calculated by means of the four-variable Modification of Diet in Renal Disease (MDRD) formula. For this IPD meta-analysis, eGFR at baseline and eGFR change during follow-up were computed by fitting linear regression models and linear mixed models in each cohort separately. Effect estimates were pooled using random effects models. Results: A total of 72 856 individuals from 16 different cohorts were included. At baseline, individuals with overt hypothyroidism (n = 704) and subclinical hypothyroidism (n = 3356) had a average (95% confidence interval) -4.07 (-6.37 to -1.78) and -2.40 (-3.78 to -1.02) mL/min/1.73 m2 lower eGFR as compared with euthyroid subjects (n = 66 542). In (subclinical) hyperthyroid subjects (n = 2254), average eGFR was 3.01 (1.50-4.52) mL/min/1.73 m2 higher. During 329 713 patient years of follow-up, eGFR did not decline more rapidly in individuals with low thyroid function compared with individuals with normal thyroid function. Conclusions: Low thyroid function is not associated with a deterioration of renal function. The cross-sectional association may be explained by renal dysfunction causing thyroid hormone alterations.

Meta-analysis across Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) consortium provides evidence for an association of serum vitamin D with pulmonary function. - Xu, Jiayi; Bartz, Traci M; Chittoor, Geetha; Eiriksdottir, Gudny; Manichaikul, Ani W; Sun, Fangui; Terzikhan, Natalie; Zhou, Xia; Booth, Sarah L; Brusselle, Guy G; de Boer, Ian H; Fornage, Myriam; et al. (Br J Nutr, 2018)
The role that vitamin D plays in pulmonary function remains uncertain. Epidemiological studies reported mixed findings for serum 25-hydroxyvitamin D (25(OH)D)-pulmonary function association. We conducted the largest cross-sectional meta-analysis of the 25(OH)D-pulmonary function association to date, based on nine European ancestry (EA) cohorts (n 22 838) and five African ancestry (AA) cohorts (n 4290) in the Cohorts for Heart and Aging Research in Genomic Epidemiology Consortium. Data were analysed using linear models by cohort and ancestry. Effect modification by smoking status (current/former/never) was tested. Results were combined using fixed-effects meta-analysis. Mean serum 25(OH)D was 68 (sd 29) nmol/l for EA and 49 (sd 21) nmol/l for AA. For each 1 nmol/l higher 25(OH)D, forced expiratory volume in the 1st second (FEV1) was higher by 1·1 ml in EA (95 % CI 0·9, 1·3; P<0·0001) and 1·8 ml (95 % CI 1·1, 2·5; P<0·0001) in AA (P race difference=0·06), and forced vital capacity (FVC) was higher by 1·3 ml in EA (95 % CI 1·0, 1·6; P<0·0001) and 1·5 ml (95 % CI 0·8, 2·3; P=0·0001) in AA (P race difference=0·56). Among EA, the 25(OH)D-FVC association was stronger in smokers: per 1 nmol/l higher 25(OH)D, FVC was higher by 1·7 ml (95 % CI 1·1, 2·3) for current smokers and 1·7 ml (95 % CI 1·2, 2·1) for former smokers, compared with 0·8 ml (95 % CI 0·4, 1·2) for never smokers. In summary, the 25(OH)D associations with FEV1 and FVC were positive in both ancestries. In EA, a stronger association was observed for smokers compared with never smokers, which supports the importance of vitamin D in vulnerable populations.

Meta-analysis of exome array data identifies six novel genetic loci for lung function. - Jackson, Victoria E; Latourelle, Jeanne C; Wain, Louise V; Smith, Albert V; Grove, Megan L; Bartz, Traci M; Obeidat, Ma'en; Province, Michael A; Gao, Wei; Qaiser, Beenish; Porteous, David J; Cassano, Patricia A; et al. (Wellcome Open Res, 2018)
Over 90 regions of the genome have been associated with lung function to date, many of which have also been implicated in chronic obstructive pulmonary disease. We carried out meta-analyses of exome array data and three lung function measures: forced expiratory volume in one second (FEV ), forced vital capacity (FVC) and the ratio of FEV to FVC (FEV /FVC). These analyses by the SpiroMeta and CHARGE consortia included 60,749 individuals of European ancestry from 23 studies, and 7,721 individuals of African Ancestry from 5 studies in the discovery stage, with follow-up in up to 111,556 independent individuals. We identified significant (P<2·8x10 ) associations with six SNPs: a nonsynonymous variant in , which is predicted to be damaging, three intronic SNPs ( and ) and two intergenic SNPs near to and Expression quantitative trait loci analyses found evidence for regulation of gene expression at three signals and implicated several genes, including and . Further interrogation of these loci could provide greater understanding of the determinants of lung function and pulmonary disease.

Multiancestry association study identifies new asthma risk loci that colocalize with immune-cell enhancer marks. - Demenais, Florence; Margaritte-Jeannin, Patricia; Barnes, Kathleen C; Cookson, William O C; Altmüller, Janine; Ang, Wei; Barr, R Graham; Beaty, Terri H; Becker, Allan B; Beilby, John; Bisgaard, Hans; Bjornsdottir, Unnur Steina; et al. (Nat Genet, 2018)
We examined common variation in asthma risk by conducting a meta-analysis of worldwide asthma genome-wide association studies (23,948 asthma cases, 118,538 controls) of individuals from ethnically diverse populations. We identified five new asthma loci, found two new associations at two known asthma loci, established asthma associations at two loci previously implicated in the comorbidity of asthma plus hay fever, and confirmed nine known loci. Investigation of pleiotropy showed large overlaps in genetic variants with autoimmune and inflammatory diseases. The enrichment in enhancer marks at asthma risk loci, especially in immune cells, suggested a major role of these loci in the regulation of immunologically related mechanisms.

Multiancestry genome-wide association study of 520,000 subjects identifies 32 loci associated with stroke and stroke subtypes. - Malik, Rainer; Chauhan, Ganesh; Traylor, Matthew; Sargurupremraj, Muralidharan; Okada, Yukinori; Mishra, Aniket; Rutten-Jacobs, Loes; Giese, Anne-Katrin; van der Laan, Sander W; Gretarsdottir, Solveig; Anderson, Christopher D; Chong, Michael; et al. (Nat Genet, 2018)
Stroke has multiple etiologies, but the underlying genes and pathways are largely unknown. We conducted a multiancestry genome-wide-association meta-analysis in 521,612 individuals (67,162 cases and 454,450 controls) and discovered 22 new stroke risk loci, bringing the total to 32. We further found shared genetic variation with related vascular traits, including blood pressure, cardiac traits, and venous thromboembolism, at individual loci (n = 18), and using genetic risk scores and linkage-disequilibrium-score regression. Several loci exhibited distinct association and pleiotropy patterns for etiological stroke subtypes. Eleven new susceptibility loci indicate mechanisms not previously implicated in stroke pathophysiology, with prioritization of risk variants and genes accomplished through bioinformatics analyses using extensive functional datasets. Stroke risk loci were significantly enriched in drug targets for antithrombotic therapy.

Multi-ethnic genome-wide association study for atrial fibrillation. - Roselli, Carolina; Chaffin, Mark D; Weng, Lu-Chen; Aeschbacher, Stefanie; Ahlberg, Gustav; Albert, Christine M; Almgren, Peter; Alonso, Alvaro; Anderson, Christopher D; Aragam, Krishna G; Arking, Dan E; Barnard, John; et al. (Nat Genet, 2018)
Atrial fibrillation (AF) affects more than 33 million individuals worldwide and has a complex heritability. We conducted the largest meta-analysis of genome-wide association studies (GWAS) for AF to date, consisting of more than half a million individuals, including 65,446 with AF. In total, we identified 97 loci significantly associated with AF, including 67 that were novel in a combined-ancestry analysis, and 3 that were novel in a European-specific analysis. We sought to identify AF-associated genes at the GWAS loci by performing RNA-sequencing and expression quantitative trait locus analyses in 101 left atrial samples, the most relevant tissue for AF. We also performed transcriptome-wide analyses that identified 57 AF-associated genes, 42 of which overlap with GWAS loci. The identified loci implicate genes enriched within cardiac developmental, electrophysiological, contractile and structural pathways. These results extend our understanding of the biological pathways underlying AF and may facilitate the development of therapeutics for AF.

Multiethnic meta-analysis identifies ancestry-specific and cross-ancestry loci for pulmonary function. - Wyss, Annah B; Sofer, Tamar; Lee, Mi Kyeong; Terzikhan, Natalie; Nguyen, Jennifer N; Lahousse, Lies; Latourelle, Jeanne C; Smith, Albert Vernon; Bartz, Traci M; Feitosa, Mary F; Gao, Wei; Ahluwalia, Tarunveer S; et al. (Nat Commun, 2018)
Nearly 100 loci have been identified for pulmonary function, almost exclusively in studies of European ancestry populations. We extend previous research by meta-analyzing genome-wide association studies of 1000 Genomes imputed variants in relation to pulmonary function in a multiethnic population of 90,715 individuals of European (N = 60,552), African (N = 8429), Asian (N = 9959), and Hispanic/Latino (N = 11,775) ethnicities. We identify over 50 additional loci at genome-wide significance in ancestry-specific or multiethnic meta-analyses. Using recent fine-mapping methods incorporating functional annotation, gene expression, and differences in linkage disequilibrium between ethnicities, we further shed light on potential causal variants and genes at known and newly identified loci. Several of the novel genes encode proteins with predicted or established drug targets, including KCNK2 and CDK12. Our study highlights the utility of multiethnic and integrative genomics approaches to extend existing knowledge of the genetics of lung function and clinical relevance of implicated loci.

Multiethnic Meta-Analysis Identifies RAI1 as a Possible Obstructive Sleep Apnea-related Quantitative Trait Locus in Men. - Chen, Han; Cade, Brian E; Gleason, Kevin J; Bjonnes, Andrew C; Stilp, Adrienne M; Sofer, Tamar; Conomos, Matthew P; Ancoli-Israel, Sonia; Arens, Raanan; Azarbarzin, Ali; Bell, Graeme I; Below, Jennifer E; et al. (Am J Respir Cell Mol Biol, 2018)
Obstructive sleep apnea (OSA) is a common heritable disorder displaying marked sexual dimorphism in disease prevalence and progression. Previous genetic association studies have identified a few genetic loci associated with OSA and related quantitative traits, but they have only focused on single ethnic groups, and a large proportion of the heritability remains unexplained. The apnea-hypopnea index (AHI) is a commonly used quantitative measure characterizing OSA severity. Because OSA differs by sex, and the pathophysiology of obstructive events differ in rapid eye movement (REM) and non-REM (NREM) sleep, we hypothesized that additional genetic association signals would be identified by analyzing the NREM/REM-specific AHI and by conducting sex-specific analyses in multiethnic samples. We performed genome-wide association tests for up to 19,733 participants of African, Asian, European, and Hispanic/Latino American ancestry in 7 studies. We identified rs12936587 on chromosome 17 as a possible quantitative trait locus for NREM AHI in men (N = 6,737; P = 1.7 × 10) but not in women (P = 0.77). The association with NREM AHI was replicated in a physiological research study (N = 67; P = 0.047). This locus overlapping the RAI1 gene and encompassing genes PEMT1, SREBF1, and RASD1 was previously reported to be associated with coronary artery disease, lipid metabolism, and implicated in Potocki-Lupski syndrome and Smith-Magenis syndrome, which are characterized by abnormal sleep phenotypes. We also identified gene-by-sex interactions in suggestive association regions, suggesting that genetic variants for AHI appear to vary by sex, consistent with the clinical observations of strong sexual dimorphism.

Novel genetic associations for blood pressure identified via gene-alcohol interaction in up to 570K individuals across multiple ancestries. - Feitosa, Mary F; Kraja, Aldi T; Chasman, Daniel I; Sung, Yun J; Winkler, Thomas W; Ntalla, Ioanna; Guo, Xiuqing; Franceschini, Nora; Cheng, Ching-Yu; Sim, Xueling; Vojinovic, Dina; Marten, Jonathan; et al. (PLoS One, 2018)
Heavy alcohol consumption is an established risk factor for hypertension; the mechanism by which alcohol consumption impact blood pressure (BP) regulation remains unknown. We hypothesized that a genome-wide association study accounting for gene-alcohol consumption interaction for BP might identify additional BP loci and contribute to the understanding of alcohol-related BP regulation. We conducted a large two-stage investigation incorporating joint testing of main genetic effects and single nucleotide variant (SNV)-alcohol consumption interactions. In Stage 1, genome-wide discovery meta-analyses in ≈131K individuals across several ancestry groups yielded 3,514 SNVs (245 loci) with suggestive evidence of association (P < 1.0 x 10-5). In Stage 2, these SNVs were tested for independent external replication in ≈440K individuals across multiple ancestries. We identified and replicated (at Bonferroni correction threshold) five novel BP loci (380 SNVs in 21 genes) and 49 previously reported BP loci (2,159 SNVs in 109 genes) in European ancestry, and in multi-ancestry meta-analyses (P < 5.0 x 10-8). For African ancestry samples, we detected 18 potentially novel BP loci (P < 5.0 x 10-8) in Stage 1 that warrant further replication. Additionally, correlated meta-analysis identified eight novel BP loci (11 genes). Several genes in these loci (e.g., PINX1, GATA4, BLK, FTO and GABBR2) have been previously reported to be associated with alcohol consumption. These findings provide insights into the role of alcohol consumption in the genetic architecture of hypertension.

Omega-3 Fatty Acids and Genome-wide Interaction Analyses Reveal DPP10-Pulmonary Function Association. - Xu, Jiayi; Gaddis, Nathan C; Bartz, Traci M; Hou, Ruixue; Manichaikul, Ani W; Pankratz, Nathan; Smith, Albert V; Sun, Fangui; Terzikhan, Natalie; Markunas, Christina A; Patchen, Bonnie K; Schu, Matthew; et al. (Am J Respir Crit Care Med, 2018)
RATIONALE: Omega-3 poly-unsaturated fatty acids (n-3 PUFAs) have anti-inflammatory properties that could benefit adults with comprised pulmonary health. OBJECTIVE: To investigate n-3 PUFA associations with spirometric measures of pulmonary function tests (PFTs) and determine underlying genetic susceptibility. METHODS: Associations of n-3 PUFA biomarkers (alpha-linolenic acid, eicosapentaenoic acid, docosapentaenoic acid [DPA], and docosahexaenoic acid [DHA]) were evaluated with PFTs (forced expiratory volume in the first second [FEV], forced vital capacity [FVC], and [FEV/FVC]) in meta-analyses across seven cohorts from the Cohorts for Heart and Aging Research in Genomic Epidemiology Consortium (N=16,134 of European or African ancestry). PFT-associated n-3 PUFAs were carried forward to genome-wide interaction analyses in the four largest cohorts (N=11,962) and replicated in one cohort (N=1,687). Cohort-specific results were combined using joint 2 degree-of-freedom (2df) meta-analyses of single nucleotide polymorphism (SNP) associations and their interactions with n-3 PUFAs. RESULTS: DPA and DHA were positively associated with FEV1 and FVC (P<0.025), with evidence for effect modification by smoking and by sex. Genome-wide analyses identified a novel association of rs11693320-an intronic DPP10 SNP-with FVC when incorporating an interaction with DHA, and the finding was replicated (P=9.4×10 across discovery and replication cohorts). The rs11693320-A allele (frequency~80%) was associated with lower FVC (P=2.1×10; β= -161.0mL), and the association was attenuated by higher DHA levels (P=2.1×10; β=36.2mL). CONCLUSIONS: We corroborated beneficial effects of n-3 PUFAs on pulmonary function. By modeling genome-wide n-3 PUFA interactions, we identified a novel DPP10 SNP association with FVC that was not detectable in much larger studies ignoring this interaction.

PR interval genome-wide association meta-analysis identifies 50 loci associated with atrial and atrioventricular electrical activity. - van Setten, Jessica; Brody, Jennifer A; Jamshidi, Yalda; Swenson, Brenton R; Butler, Anne M; Campbell, Harry; Del Greco, Fabiola M; Evans, Daniel S; Gibson, Quince; Gudbjartsson, Daniel F; Kerr, Kathleen F; Krijthe, Bouwe P; et al. (Nat Commun, 2018)
Electrocardiographic PR interval measures atrio-ventricular depolarization and conduction, and abnormal PR interval is a risk factor for atrial fibrillation and heart block. Our genome-wide association study of over 92,000 European-descent individuals identifies 44 PR interval loci (34 novel). Examination of these loci reveals known and previously not-yet-reported biological processes involved in cardiac atrial electrical activity. Genes in these loci are over-represented in cardiac disease processes including heart block and atrial fibrillation. Variants in over half of the 44 loci were associated with atrial or blood transcript expression levels, or were in high linkage disequilibrium with missense variants. Six additional loci were identified either by meta-analysis of ~105,000 African and European-descent individuals and/or by pleiotropic analyses combining PR interval with heart rate, QRS interval, and atrial fibrillation. These findings implicate developmental pathways, and identify transcription factors, ion-channel genes, and cell-junction/cell-signaling proteins in atrio-ventricular conduction, identifying potential targets for drug development.

Predictive value for cardiovascular events of common carotid intima media thickness and its rate of change in individuals at high cardiovascular risk - Results from the PROG-IMT collaboration. - Lorenz, Matthias W; Gao, Lu; Ziegelbauer, Kathrin; Norata, Giuseppe Danilo; Empana, Jean Philippe; Schmidtmann, Irene; Lin, Hung-Ju; McLachlan, Stela; Bokemark, Lena; Ronkainen, Kimmo; Amato, Mauro; Schminke, Ulf; et al. (PLoS One, 2018)
AIMS: Carotid intima media thickness (CIMT) predicts cardiovascular (CVD) events, but the predictive value of CIMT change is debated. We assessed the relation between CIMT change and events in individuals at high cardiovascular risk. METHODS AND RESULTS: From 31 cohorts with two CIMT scans (total n = 89070) on average 3.6 years apart and clinical follow-up, subcohorts were drawn: (A) individuals with at least 3 cardiovascular risk factors without previous CVD events, (B) individuals with carotid plaques without previous CVD events, and (C) individuals with previous CVD events. Cox regression models were fit to estimate the hazard ratio (HR) of the combined endpoint (myocardial infarction, stroke or vascular death) per standard deviation (SD) of CIMT change, adjusted for CVD risk factors. These HRs were pooled across studies. In groups A, B and C we observed 3483, 2845 and 1165 endpoint events, respectively. Average common CIMT was 0.79mm (SD 0.16mm), and annual common CIMT change was 0.01mm (SD 0.07mm), both in group A. The pooled HR per SD of annual common CIMT change (0.02 to 0.43mm) was 0.99 (95% confidence interval: 0.95-1.02) in group A, 0.98 (0.93-1.04) in group B, and 0.95 (0.89-1.04) in group C. The HR per SD of common CIMT (average of the first and the second CIMT scan, 0.09 to 0.75mm) was 1.15 (1.07-1.23) in group A, 1.13 (1.05-1.22) in group B, and 1.12 (1.05-1.20) in group C. CONCLUSIONS: We confirm that common CIMT is associated with future CVD events in individuals at high risk. CIMT change does not relate to future event risk in high-risk individuals.
Keywords: Aged; Cardiovascular Diseases; Carotid Intima-Media Thickness; Female; Humans; Intersectoral Collaboration; Male; Middle Aged; Prognosis; Risk Factors

Refining the accuracy of validated target identification through coding variant fine-mapping in type 2 diabetes. - Mahajan, Anubha; Wessel, Jennifer; Willems, Sara M; Zhao, Wei; Robertson, Neil R; Chu, Audrey Y; Gan, Wei; Kitajima, Hidetoshi; Taliun, Daniel; Rayner, N William; Guo, Xiuqing; Lu, Yingchang; et al. (Nat Genet, 2018)
We aggregated coding variant data for 81,412 type 2 diabetes cases and 370,832 controls of diverse ancestry, identifying 40 coding variant association signals (P < 2.2 × 10); of these, 16 map outside known risk-associated loci. We make two important observations. First, only five of these signals are driven by low-frequency variants: even for these, effect sizes are modest (odds ratio ≤1.29). Second, when we used large-scale genome-wide association data to fine-map the associated variants in their regional context, accounting for the global enrichment of complex trait associations in coding sequence, compelling evidence for coding variant causality was obtained for only 16 signals. At 13 others, the associated coding variants clearly represent 'false leads' with potential to generate erroneous mechanistic inference. Coding variant associations offer a direct route to biological insight for complex diseases and identification of validated therapeutic targets; however, appropriate mechanistic inference requires careful specification of their causal contribution to disease predisposition.

The relation between thyroid function and anemia: a pooled analysis of individual participant data. - Wopereis, Daisy M; Du Puy, Robert S; van Heemst, Diana; Walsh, John P; Bremner, Alexandra; Bakker, Stephan J L; Bauer, Douglas C; Cappola, Anne R; Ceresini, Graziano; Degryse, Jean; Dullaart, Robin P F; Feller, Martin; et al. (J Clin Endocrinol Metab, 2018)
Context: Anemia and thyroid dysfunction often co-occur and both increase with age. Human data on the relationship between thyroid disease and anemia are scarce. Objective: To investigate the cross-sectional and longitudinal associations between clinical thyroid status and anemia. Design: Individual participant data meta-analysis. Setting: Sixteen cohorts participating in the Thyroid Studies Collaboration (n=42 162). Main outcome measures: Primary outcome measure was anemia (hemoglobin <130 g/L in men and <120 g/L in women). Results: Cross-sectionally, participants with abnormal thyroid status had an increased risk of having anemia compared with euthyroid participants (overt hypothyroidism, pooled odds ratio 1.84 [95% CI: 1.35-2.50], subclinical hypothyroidism 1.21 [1.02-1.43], subclinical hyperthyroidism 1.27 [1.03-1.57], overt hyperthyroidism 1.69 [1.00-2.87]). Hemoglobin levels were lower in all groups compared to participants with euthyroidism. In the longitudinal analyses (n=25,466 from 14 cohorts), the pooled hazard ratio for the risk of development of anemia was 1.38 [95% CI: 0.86-2.20] for overt hypothyroidism, 1.18 [1.00-1.38] for subclinical hypothyroidism, 1.15 [0.94-1.42] for subclinical hyperthyroidism and 1.47 [0.91-2.38] for overt hyperthyroidism. Sensitivity analyses excluding thyroid medication or high levels of C-reactive protein yielded similar results. No differences in mean annual change in hemoglobin levels were observed between the thyroid hormone status groups. Conclusion: Higher odds of having anemia were observed in both participants with hypothyroid function and hyperthyroid function. In addition, reduced thyroid function at baseline showed a trend of increased risk of developing anemia during follow-up. It remains to be assessed in a randomized controlled trial whether treatment is effective in reducing anemia.

Relationship of Estimated GFR and Albuminuria to Concurrent Laboratory Abnormalities: An Individual Participant Data Meta-analysis in a Global Consortium. - Inker, Lesley A; Grams, Morgan E; Levey, Andrew S; Coresh, Josef; Cirillo, Massimo; Collins, John F; Gansevoort, Ron T; Gutierrez, Orlando M; Hamano, Takayuki; Heine, Gunnar H; Ishikawa, Shizukiyo; Jee, Sun Ha; et al. (Am J Kidney Dis, 2018)
RATIONALE & OBJECTIVE: Chronic kidney disease (CKD) is complicated by abnormalities that reflect disruption in filtration, tubular, and endocrine functions of the kidney. Our aim was to explore the relationship of specific laboratory result abnormalities and hypertension with the estimated glomerular filtration rate (eGFR) and albuminuria CKD staging framework. STUDY DESIGN: Cross-sectional individual participant-level analyses in a global consortium. SETTING & STUDY POPULATIONS: 17 CKD and 38 general population and high-risk cohorts. SELECTION CRITERIA FOR STUDIES: Cohorts in the CKD Prognosis Consortium with data for eGFR and albuminuria, as well as a measurement of hemoglobin, bicarbonate, phosphorus, parathyroid hormone, potassium, or calcium, or hypertension. DATA EXTRACTION: Data were obtained and analyzed between July 2015 and January 2018. ANALYTICAL APPROACH: We modeled the association of eGFR and albuminuria with hemoglobin, bicarbonate, phosphorus, parathyroid hormone, potassium, and calcium values using linear regression and with hypertension and categorical definitions of each abnormality using logistic regression. Results were pooled using random-effects meta-analyses. RESULTS: The CKD cohorts (n=254,666 participants) were 27% women and 10% black, with a mean age of 69 (SD, 12) years. The general population/high-risk cohorts (n=1,758,334) were 50% women and 2% black, with a mean age of 50 (16) years. There was a strong graded association between lower eGFR and all laboratory result abnormalities (ORs ranging from 3.27 [95% CI, 2.68-3.97] to 8.91 [95% CI, 7.22-10.99] comparing eGFRs of 15 to 29 with eGFRs of 45 to 59mL/min/1.73m), whereas albuminuria had equivocal or weak associations with abnormalities (ORs ranging from 0.77 [95% CI, 0.60-0.99] to 1.92 [95% CI, 1.65-2.24] comparing urinary albumin-creatinine ratio > 300 vs < 30mg/g). LIMITATIONS: Variations in study era, health care delivery system, typical diet, and laboratory assays. CONCLUSIONS: Lower eGFR was strongly associated with higher odds of multiple laboratory result abnormalities. Knowledge of risk associations might help guide management in the heterogeneous group of patients with CKD.

Risk thresholds for alcohol consumption: combined analysis of individual-participant data for 599 912 current drinkers in 83 prospective studies. - Wood, Angela M; Kaptoge, Stephen; Butterworth, Adam S; Willeit, Peter; Warnakula, Samantha; Bolton, Thomas; Paige, Ellie; Paul, Dirk S; Sweeting, Michael; Burgess, Stephen; Bell, Steven; Astle, William; et al. (Lancet, 2018)
BACKGROUND: Low-risk limits recommended for alcohol consumption vary substantially across different national guidelines. To define thresholds associated with lowest risk for all-cause mortality and cardiovascular disease, we studied individual-participant data from 599 912 current drinkers without previous cardiovascular disease. METHODS: We did a combined analysis of individual-participant data from three large-scale data sources in 19 high-income countries (the Emerging Risk Factors Collaboration, EPIC-CVD, and the UK Biobank). We characterised dose-response associations and calculated hazard ratios (HRs) per 100 g per week of alcohol (12·5 units per week) across 83 prospective studies, adjusting at least for study or centre, age, sex, smoking, and diabetes. To be eligible for the analysis, participants had to have information recorded about their alcohol consumption amount and status (ie, non-drinker vs current drinker), plus age, sex, history of diabetes and smoking status, at least 1 year of follow-up after baseline, and no baseline history of cardiovascular disease. The main analyses focused on current drinkers, whose baseline alcohol consumption was categorised into eight predefined groups according to the amount in grams consumed per week. We assessed alcohol consumption in relation to all-cause mortality, total cardiovascular disease, and several cardiovascular disease subtypes. We corrected HRs for estimated long-term variability in alcohol consumption using 152 640 serial alcohol assessments obtained some years apart (median interval 5·6 years [5th-95th percentile 1·04-13·5]) from 71 011 participants from 37 studies. FINDINGS: In the 599 912 current drinkers included in the analysis, we recorded 40 310 deaths and 39 018 incident cardiovascular disease events during 5·4 million person-years of follow-up. For all-cause mortality, we recorded a positive and curvilinear association with the level of alcohol consumption, with the minimum mortality risk around or below 100 g per week. Alcohol consumption was roughly linearly associated with a higher risk of stroke (HR per 100 g per week higher consumption 1·14, 95% CI, 1·10-1·17), coronary disease excluding myocardial infarction (1·06, 1·00-1·11), heart failure (1·09, 1·03-1·15), fatal hypertensive disease (1·24, 1·15-1·33); and fatal aortic aneurysm (1·15, 1·03-1·28). By contrast, increased alcohol consumption was log-linearly associated with a lower risk of myocardial infarction (HR 0·94, 0·91-0·97). In comparison to those who reported drinking >0-≤100 g per week, those who reported drinking >100-≤200 g per week, >200-≤350 g per week, or >350 g per week had lower life expectancy at age 40 years of approximately 6 months, 1-2 years, or 4-5 years, respectively. INTERPRETATION: In current drinkers of alcohol in high-income countries, the threshold for lowest risk of all-cause mortality was about 100 g/week. For cardiovascular disease subtypes other than myocardial infarction, there were no clear risk thresholds below which lower alcohol consumption stopped being associated with lower disease risk. These data support limits for alcohol consumption that are lower than those recommended in most current guidelines. FUNDING: UK Medical Research Council, British Heart Foundation, National Institute for Health Research, European Union Framework 7, and European Research Council.

Sleep characteristics that predict atrial fibrillation. - Christensen, Matthew A; Dixit, Shalini; Dewland, Thomas A; Whitman, Isaac R; Nah, Gregory; Vittinghoff, Eric; Mukamal, Kenneth J; Redline, Susan; Robbins, John A; Newman, Anne B; Patel, Sanjay R; Magnani, Jared W; et al. (Heart Rhythm, 2018)
BACKGROUND: The relationship between sleep disruption, independent of obstructive sleep apnea (OSA), and atrial fibrillation (AF) is unknown. OBJECTIVE: The purpose of this study was to determine whether poor sleep itself is a risk factor for AF. METHODS: We first performed an analysis of participants in the Health eHeart Study and validated those findings in the longitudinal Cardiovascular Health Study, including a subset of patients undergoing polysomnography. To determine whether the observed relationships readily translated to medical practice, we examined 2005-2009 data from the California Healthcare Cost and Utilization Project. RESULTS: Among 4553 Health eHeart participants, the 526 with AF exhibited more frequent nighttime awakening (odd ratio [OR] 1.47; 95% confidence interval [CI] 1.14-1.89; P = .003). In 5703 Cardiovascular Health Study participants followed for a median 11.6 years, frequent nighttime awakening predicted a 33% greater risk of AF (hazard ratio [HR] 1.33; 95% CI 1.17-1.51; P <.001). In patients with polysomnography (N = 1127), every standard deviation percentage decrease in rapid eye movement (REM) sleep was associated with a 18% higher risk of developing AF (HR 1.18; 95% CI 1.00-1.38; P = .047). Among 14,330,651 California residents followed for a median 3.9 years, an insomnia diagnosis predicted a 36% increased risk of new AF (HR 1.36; 95% CI 1.30-1.42; P <.001). CONCLUSION: Sleep disruption consistently predicted AF before and after adjustment for OSA and other potential confounders across several different populations. Sleep quality itself may be important in the pathogenesis of AF, potentially representing a novel target for prevention.

Study of 300,486 individuals identifies 148 independent genetic loci influencing general cognitive function. - Davies, Gail; Lam, Max; Harris, Sarah E; Trampush, Joey W; Luciano, Michelle; Hill, W David; Hagenaars, Saskia P; Ritchie, Stuart J; Marioni, Riccardo E; Fawns-Ritchie, Chloe; Liewald, David C M; Okely, Judith A; et al. (Nat Commun, 2018)
General cognitive function is a prominent and relatively stable human trait that is associated with many important life outcomes. We combine cognitive and genetic data from the CHARGE and COGENT consortia, and UK Biobank (total N = 300,486; age 16-102) and find 148 genome-wide significant independent loci (P < 5 × 10) associated with general cognitive function. Within the novel genetic loci are variants associated with neurodegenerative and neurodevelopmental disorders, physical and psychiatric illnesses, and brain structure. Gene-based analyses find 709 genes associated with general cognitive function. Expression levels across the cortex are associated with general cognitive function. Using polygenic scores, up to 4.3% of variance in general cognitive function is predicted in independent samples. We detect significant genetic overlap between general cognitive function, reaction time, and many health variables including eyesight, hypertension, and longevity. In conclusion we identify novel genetic loci and pathways contributing to the heritability of general cognitive function.

Sugar-sweetened beverage intake associations with fasting glucose and insulin concentrations are not modified by selected genetic variants in a ChREBP-FGF21 pathway: a meta-analysis. - McKeown, Nicola M; Dashti, Hassan S; Ma, Jiantao; Haslam, Danielle E; Kiefte-de Jong, Jessica C; Smith, Caren E; Tanaka, Toshiko; Graff, Mariaelisa; Lemaitre, Rozenn N; Rybin, Denis; Sonestedt, Emily; Frazier-Wood, Alexis C; et al. (Diabetologia, 2018)
AIMS/HYPOTHESIS: Sugar-sweetened beverages (SSBs) are a major dietary contributor to fructose intake. A molecular pathway involving the carbohydrate responsive element-binding protein (ChREBP) and the metabolic hormone fibroblast growth factor 21 (FGF21) may influence sugar metabolism and, thereby, contribute to fructose-induced metabolic disease. We hypothesise that common variants in 11 genes involved in fructose metabolism and the ChREBP-FGF21 pathway may interact with SSB intake to exacerbate positive associations between higher SSB intake and glycaemic traits. METHODS: Data from 11 cohorts (six discovery and five replication) in the CHARGE (Cohorts for Heart and Aging Research in Genomic Epidemiology) Consortium provided association and interaction results from 34,748 adults of European descent. SSB intake (soft drinks, fruit punches, lemonades or other fruit drinks) was derived from food-frequency questionnaires and food diaries. In fixed-effects meta-analyses, we quantified: (1) the associations between SSBs and glycaemic traits (fasting glucose and fasting insulin); and (2) the interactions between SSBs and 18 independent SNPs related to the ChREBP-FGF21 pathway. RESULTS: In our combined meta-analyses of discovery and replication cohorts, after adjustment for age, sex, energy intake, BMI and other dietary covariates, each additional serving of SSB intake was associated with higher fasting glucose (β ± SE 0.014 ± 0.004 [mmol/l], p = 1.5 × 10-3) and higher fasting insulin (0.030 ± 0.005 [log e pmol/l], p = 2.0 × 10-10). No significant interactions on glycaemic traits were observed between SSB intake and selected SNPs. While a suggestive interaction was observed in the discovery cohorts with a SNP (rs1542423) in the β-Klotho (KLB) locus on fasting insulin (0.030 ± 0.011 log e pmol/l, uncorrected p = 0.006), results in the replication cohorts and combined meta-analyses were non-significant. CONCLUSIONS/INTERPRETATION: In this large meta-analysis, we observed that SSB intake was associated with higher fasting glucose and insulin. Although a suggestive interaction with a genetic variant in the ChREBP-FGF21 pathway was observed in the discovery cohorts, this observation was not confirmed in the replication analysis. TRIAL REGISTRATION: Trials related to this study were registered at clinicaltrials.gov as NCT00005131 (Atherosclerosis Risk in Communities), NCT00005133 (Cardiovascular Health Study), NCT00005121 (Framingham Offspring Study), NCT00005487 (Multi-Ethnic Study of Atherosclerosis) and NCT00005152 (Nurses' Health Study).

Trans-ethnic analysis of metabochip data identifies two new loci associated with BMI. - Gong, J; Nishimura, K K; Fernandez-Rhodes, L; Haessler, J; Bien, S; Graff, M; Lim, U; Lu, Y; Gross, M; Fornage, M; Yoneyama, S; Isasi, C R; et al. (Int J Obes (Lond), 2018)
OBJECTIVE: Body mass index (BMI) is commonly used to assess obesity, which is associated with numerous diseases and negative health outcomes. BMI has been shown to be a heritable, polygenic trait, with close to 100 loci previously identified and replicated in multiple populations. We aim to replicate known BMI loci and identify novel associations in a trans-ethnic study population. SUBJECTS: Using eligible participants from the Population Architecture using Genomics and Epidemiology consortium, we conducted a trans-ethnic meta-analysis of 102 514 African Americans, Hispanics, Asian/Native Hawaiian, Native Americans and European Americans. Participants were genotyped on over 200 000 SNPs on the Illumina Metabochip custom array, or imputed into the 1000 Genomes Project (Phase I). Linear regression of the natural log of BMI, adjusting for age, sex, study site (if applicable), and ancestry principal components, was conducted for each race/ethnicity within each study cohort. Race/ethnicity-specific, and combined meta-analyses used fixed-effects models. RESULTS: We replicated 15 of 21 BMI loci included on the Metabochip, and identified two novel BMI loci at 1q41 (rs2820436) and 2q31.1 (rs10930502) at the Metabochip-wide significance threshold (P<2.5 × 10). Bioinformatic functional investigation of SNPs at these loci suggests a possible impact on pathways that regulate metabolism and adipose tissue. CONCLUSION: Conducting studies in genetically diverse populations continues to be a valuable strategy for replicating known loci and uncovering novel BMI associations.

Trans-ethnic Evaluation Identifies Novel Low Frequency Loci Associated with 25-Hydroxyvitamin D Concentrations. - Hong, Jaeyoung; Hatchell, Kathryn E; Bradfield, Jonathan P; Andrew, Bjonnes; Alessandra, Chesi; Chao-Qiang, Lai; Langefeld, Carl D; Lu, Lingyi; Lu, Yingchang; Lutsey, Pamela L; Musani, Solomon K; Nalls, Mike A; et al. (J Clin Endocrinol Metab, 2018)
Context: Vitamin D inadequacy is common in the adult population of the United States. While the genetic determinants underlying vitamin D inadequacy have been studied in people of European ancestry, less is known in Hispanic or African ancestry populations. Objective: The TRANSCEN-D (TRANS-ethniC Evaluation of vitamiN D GWAS) consortium was assembled to replicate genetic associations with 25-hydroxyvitamin D (25(OH)D) concentrations from the meta-analyses of European ancestry (SUNLIGHT) and to identify novel genetic variants related to vitamin D concentrations in African and Hispanic ancestries. Design: Ancestry-specific (Hispanic and African) and trans-ethnic (Hispanic, African and European) meta-analyses were performed using the METAL software. Patients or Other Participants: In total, 8,541 African-American and 3,485 Hispanic-American (from North America) participants from twelve cohorts, and 16,124 European participants from SUNLIGHT were included in the study. Main Outcome Measure(s): Blood concentrations of 25(OH)D were measured for all participants. Results: Ancestry-specific analyses in African and Hispanic Americans replicated SNPs in GC (2 and 4 SNPs, respectively). A potentially novel SNP (rs79666294) near the KIF4B gene was identified in the African-American cohort. Trans-ethnic evaluation replicated GC and DHCR7 region SNPs. Additionally, the trans-ethnic analyses revealed novel SNPs rs719700 and rs1410656 near the ANO6/ARID2 and HTR2A genes, respectively. Conclusions: Ancestry-specific and trans-ethnic GWAS of 25(OH)D confirmed findings in GC and DHCR7 for African and Hispanic American samples and revealed novel findings near KIF4B, ANO6/ARID2, and HTR2A. The biological mechanisms that link these regions with 25(OH)D metabolism require further investigation.

Validation of the REGARDS Severe Sepsis Risk Score. - Wang, Henry E; Donnelly, John P; Yende, Sachin; Levitan, Emily B; Shapiro, Nathan I; Dai, Yuling; Zhao, Hong; Heiss, Gerardo; Odden, Michelle; Newman, Anne; Safford, Monika (J Clin Med, 2018)
There are no validated systems for characterizing long-term risk of severe sepsis in community-dwelling adults. We tested the ability of the REasons for Geographic and Racial Differences in Stroke-Severe Sepsis Risk Score (REGARDS-SSRS) to predict 10-year severe sepsis risk in separate cohorts of community-dwelling adults. We internally tested the REGARDS-SSRS on the REGARDS-Medicare subcohort. We then externally validated the REGARDS-SSRS using (1) the Cardiovascular Health Study (CHS) and (2) the Atherosclerosis Risk in Communities (ARIC) cohorts. Participants included community-dwelling adults: REGARDS-Medicare, age ≥65 years, = 9522; CHS, age ≥65 years, = 5888; ARIC, age 45⁻64 years, = 11,584. The primary exposure was 10-year severe sepsis risk, predicted by the REGARDS-SSRS from participant sociodemographics, health behaviors, chronic medical conditions and select biomarkers. The primary outcome was first severe sepsis hospitalizations, defined as the concurrent presence of ICD-9 discharge diagnoses for a serious infection and organ dysfunction. Median SSRS in the cohorts were: REGARDS-Medicare 11 points (IQR 7⁻16), CHS 10 (IQR 6⁻15), ARIC 7 (IQR 5⁻10). Severe sepsis incidence rates were: REGARDS-Medicare 30.7 per 1000 person-years (95% CI: 29.2⁻32.2); CHS 11.9 (10.9⁻12.9); ARIC 6.8 (6.3⁻7.3). SSRS discrimination for first severe sepsis events were: REGARDS-Medicare C-statistic 0.704 (95% CI: 0.691⁻0.718), CHS 0.696 (0.675⁻0.716), ARIC 0.697 (0.677⁻0.716). The REGARDS-SRSS may potentially play a role in identifying community-dwelling adults at high severe sepsis risk.

Whole exome sequencing study identifies novel rare and common Alzheimer's-Associated variants involved in immune response and transcriptional regulation. - Bis, Joshua C; Jian, Xueqiu; Kunkle, Brian W; Chen, Yuning; Hamilton-Nelson, Kara L; Bush, William S; Salerno, William J; Lancour, Daniel; Ma, Yiyi; Renton, Alan E; Marcora, Edoardo; Farrell, John J; et al. (Mol Psychiatry, 2018)
The Alzheimer's Disease Sequencing Project (ADSP) undertook whole exome sequencing in 5,740 late-onset Alzheimer disease (AD) cases and 5,096 cognitively normal controls primarily of European ancestry (EA), among whom 218 cases and 177 controls were Caribbean Hispanic (CH). An age-, sex- and APOE based risk score and family history were used to select cases most likely to harbor novel AD risk variants and controls least likely to develop AD by age 85 years. We tested ~1.5 million single nucleotide variants (SNVs) and 50,000 insertion-deletion polymorphisms (indels) for association to AD, using multiple models considering individual variants as well as gene-based tests aggregating rare, predicted functional, and loss of function variants. Sixteen single variants and 19 genes that met criteria for significant or suggestive associations after multiple-testing correction were evaluated for replication in four independent samples; three with whole exome sequencing (2,778 cases, 7,262 controls) and one with genome-wide genotyping imputed to the Haplotype Reference Consortium panel (9,343 cases, 11,527 controls). The top findings in the discovery sample were also followed-up in the ADSP whole-genome sequenced family-based dataset (197 members of 42 EA families and 501 members of 157 CH families). We identified novel and predicted functional genetic variants in genes previously associated with AD. We also detected associations in three novel genes: IGHG3 (p = 9.8 × 10), an immunoglobulin gene whose antibodies interact with β-amyloid, a long non-coding RNA AC099552.4 (p = 1.2 × 10), and a zinc-finger protein ZNF655 (gene-based p = 5.0 × 10). The latter two suggest an important role for transcriptional regulation in AD pathogenesis.

Whole genome sequencing of Caribbean Hispanic families with late-onset Alzheimer's disease. - Vardarajan, Badri N; Barral, Sandra; Jaworski, James; Beecham, Gary W; Blue, Elizabeth; Tosto, Giuseppe; Reyes-Dumeyer, Dolly; Medrano, Martin; Lantigua, Rafael; Naj, Adam; Thornton, Timothy; DeStefano, Anita; et al. (Ann Clin Transl Neurol, 2018)
Objective: To identify rare causal variants underlying known loci that segregate with late-onset Alzheimer's disease (LOAD) in multiplex families. Methods: We analyzed whole genome sequences (WGS) from 351 members of 67 Caribbean Hispanic (CH) families from Dominican Republic and New York multiply affected by LOAD. Members of 67 CH and additional 47 Caucasian families underwent WGS as a part of the Alzheimer's Disease Sequencing Project (ADSP). All members of 67 CH families, an additional 48 CH families and an independent CH case-control cohort were subsequently genotyped for validation. Patients met criteria for LOAD, and controls were determined to be dementia free. We investigated rare variants segregating within families and gene-based associations with disease within LOAD GWAS loci. Results: A variant in p.R434W, segregated significantly with LOAD in two large families (OR = 5.77, 95% CI: 1.07-30.9, = 0.041). In addition, missense mutations in and under previously reported linkage peaks at 7q14.3 and 11q12.3 segregated completely in one family and in follow-up genotyping both were nominally significant ( < 0.05). We also identified rare variants in a number of genes associated with LOAD in prior genome wide association studies, including ( = 0.049), ( = 0.0098) and ( = 0.040). Conclusions and Relevance: Rare variants in multiple genes influence the risk of LOAD disease in multiplex families. These results suggest that rare variants may underlie loci identified in genome wide association studies.

Whole-exome sequencing in 20,197 persons for rare variants in Alzheimer's disease. - Raghavan, Neha S; Brickman, Adam M; Andrews, Howard; Manly, Jennifer J; Schupf, Nicole; Lantigua, Rafael; Wolock, Charles J; Kamalakaran, Sitharthan; Petrovski, Slave; Tosto, Giuseppe; Vardarajan, Badri N; Goldstein, David B; et al. (Ann Clin Transl Neurol, 2018)
Objective: The genetic bases of Alzheimer's disease remain uncertain. An international effort to fully articulate genetic risks and protective factors is underway with the hope of identifying potential therapeutic targets and preventive strategies. The goal here was to identify and characterize the frequency and impact of rare and ultra-rare variants in Alzheimer's disease, using whole-exome sequencing in 20,197 individuals. Methods: We used a gene-based collapsing analysis of loss-of-function ultra-rare variants in a case-control study design with data from the Washington Heights-Inwood Columbia Aging Project, the Alzheimer's Disease Sequencing Project and unrelated individuals from the Institute of Genomic Medicine at Columbia University. Results: We identified 19 cases carrying extremely rare loss-of-function variants among a collection of 6,965 cases and a single loss-of-function variant among 13,252 controls ( = 2.17 × 10; OR: 36.2 [95% CI: 5.8-1493.0]). Age-at-onset was 7 years earlier for patients with qualifying variant compared with noncarriers. No other gene attained a study-wide level of statistical significance, but multiple top-ranked genes, including , and were among candidates for follow-up studies. Interpretation: This study implicates ultra-rare, loss-of-function variants in as a significant genetic risk factor for Alzheimer's disease and provides a comprehensive dataset comparing the burden of rare variation in nearly all human genes in Alzheimer's disease cases and controls. This is the first investigation to establish a genome-wide statistically significant association between multiple extremely rare loss-of-function variants in and Alzheimer's disease in a large whole-exome study of unrelated cases and controls.

The Accuracy of Cardiovascular Pooled Cohort Risk Estimates in U.S. Older Adults. - Nanna, Michael G; Peterson, Eric D; Wojdyla, Daniel; Navar, Ann Marie (J Gen Intern Med, 2019)
BACKGROUND: The ACC/AHA guidelines for primary prevention rely on the Pooled Cohort Risk Equations (PCE) risk estimates of atherosclerotic cardiovascular disease (ASCVD) to guide treatment decisions. In light of the PCE being derived in younger populations, their accuracy in older adults is uncertain. OBJECTIVE: To evaluate the predictive accuracy and calibration of the PCE in older individuals. DESIGN AND SETTING: We estimated CVD predicted and observed risk among individuals from four large prospective cohort studies: Cardiovascular Health Study, Multiethnic Study of Atherosclerosis, Framingham Original, and Framingham Offspring. PARTICIPANTS: 12,527 overall individuals without ASCVD, including 9864 individuals aged 40-74 years and 2663 aged ≥75 years. MEASUREMENTS: We examined the operating characteristics of the PCE to estimate 5-year risk of stroke, MI, and CHD death overall and by age and sex strata. The associations between individual components of the PCE and cardiovascular events by age group (≥75 vs 40-74 years) were also evaluated. RESULTS: The PCE had low discrimination for 5-year ASCVD risk in older (≥75 years) (c-statistic = 0.62, 95% CI 0.60-0.65) vs. younger (40-74 years) adults (c-statistic = 0.75, 95% CI 0.73-0.76). Calibration of the PCE was suboptimal in both older and younger adults, overestimating risk in the highest risk groups. Performance of the PCE in older adults was similarly poor when stratified by sex and age ≥ 80 years. LIMITATIONS: Since the PCE were derived from similar cohorts, though using different age groups and exams, this analysis likely overestimates the performance of the PCE. CONCLUSION: The performance of the PCE for ASCVD risk estimation in older adults is suboptimal; new models to effectively risk-stratify older adults are needed.

Admixture mapping identifies novel loci for obstructive sleep apnea in Hispanic/Latino Americans. - Wang, Heming; Cade, Brian E; Sofer, Tamar; Sands, Scott A; Chen, Han; Browning, Sharon R; Stilp, Adrienne M; Louie, Tin L; Thornton, Timothy A; Johnson, W Craig; Below, Jennifer E; Conomos, Matthew P; et al. (Hum Mol Genet, 2019)
Obstructive sleep apnea (OSA) is a common disorder associated with increased risk of cardiovascular disease and mortality. Its prevalence and severity vary across ancestral background. Although OSA traits are heritable, few genetic associations have been identified. To identify genetic regions associated with OSA and improve statistical power, we applied admixture mapping on three primary OSA traits [the apnea hypopnea index (AHI), overnight average oxyhemoglobin saturation (SaO2) and percentage time SaO2 < 90%] and a secondary trait (respiratory event duration) in a Hispanic/Latino American population study of 11 575 individuals with significant variation in ancestral background. Linear mixed models were performed using previously inferred African, European and Amerindian local genetic ancestry markers. Global African ancestry was associated with a lower AHI, higher SaO2 and shorter event duration. Admixture mapping analysis of the primary OSA traits identified local African ancestry at the chromosomal region 2q37 as genome-wide significantly associated with AHI (P < 5.7 × 10-5), and European and Amerindian ancestries at 18q21 suggestively associated with both AHI and percentage time SaO2 < 90% (P < 10-3). Follow-up joint ancestry-SNP association analyses identified novel variants in ferrochelatase (FECH), significantly associated with AHI and percentage time SaO2 < 90% after adjusting for multiple tests (P < 8 × 10-6). These signals contributed to the admixture mapping associations and were replicated in independent cohorts. In this first admixture mapping study of OSA, novel associations with variants in the iron/heme metabolism pathway suggest a role for iron in influencing respiratory traits underlying OSA.

Albuminuria, Lung Function Decline, and Risk of Incident Chronic Obstructive Pulmonary Disease. The NHLBI Pooled Cohorts Study. - Oelsner, Elizabeth C; Balte, Pallavi P; Grams, Morgan E; Cassano, Patricia A; Jacobs, David R; Barr, R Graham; Burkart, Kristin M; Kalhan, Ravi; Kronmal, Richard; Loehr, Laura R; O'Connor, George T; Schwartz, Joseph E; et al. (Am J Respir Crit Care Med, 2019)
RATIONALE: Chronic lower respiratory diseases (CLRDs), including chronic obstructive pulmonary disease (COPD) and asthma, are the fourth leading cause of death. Prior studies suggest that albuminuria, a biomarker of endothelial injury, is increased in patients with COPD. OBJECTIVES: To test whether albuminuria was associated with lung function decline and incident CLRDs. METHODS: Six U.S. population-based cohorts were harmonized and pooled. Participants with prevalent clinical lung disease were excluded. Albuminuria (urine albumin-to-creatinine ratio) was measured in spot samples. Lung function was assessed by spirometry. Incident CLRD-related hospitalizations and deaths were classified via adjudication and/or administrative criteria. Mixed and proportional hazards models were used to test individual-level associations adjusted for age, height, weight, sex, race/ethnicity, education, birth year, cohort, smoking status, pack-years of smoking, renal function, hypertension, diabetes, and medications. MEASUREMENTS AND MAIN RESULTS: Among 10,961 participants with preserved lung function, mean age at albuminuria measurement was 60 years, 51% were never-smokers, median albuminuria was 5.6 mg/g, and mean FEV decline was 31.5 ml/yr. For each SD increase in log-transformed albuminuria, there was 2.81% greater FEV decline (95% confidence interval [CI], 0.86-4.76%; P = 0.0047), 11.02% greater FEV/FVC decline (95% CI, 4.43-17.62%; P = 0.0011), and 15% increased hazard of incident spirometry-defined moderate-to-severe COPD (95% CI, 2-31%, P = 0.0021). Each SD log-transformed albuminuria increased hazards of incident COPD-related hospitalization/mortality by 26% (95% CI, 18-34%, P < 0.0001) among 14,213 participants followed for events. Asthma events were not significantly associated. Associations persisted in participants without current smoking, diabetes, hypertension, or cardiovascular disease. CONCLUSIONS: Albuminuria was associated with greater lung function decline, incident spirometry-defined COPD, and incident COPD-related events in a U.S. population-based sample.

Alcohol consumption and leukocyte telomere length. - Dixit, Shalini; Whooley, Mary A; Vittinghoff, Eric; Roberts, Jason D; Heckbert, Susan R; Fitzpatrick, Annette L; Lin, Jue; Leung, Cindy; Mukamal, Kenneth J; Marcus, Gregory M (Sci Rep, 2019)
The relationship between alcohol consumption and mortality generally exhibits a U-shaped curve. The longevity observed with moderate alcohol consumption may be explained by other confounding factors, and, if such a relationship is present, the mechanism is not well understood. Indeed, the optimal amount of alcohol consumption for health has yet to be determined. Leukocyte telomere length is an emerging quantifiable marker of biological age and health, and a shorter telomere length is a predictor of increased mortality. Because leukocyte telomere length is a quantifiable and objectively measurable biomarker of aging, we sought to identify the amount of alcohol consumption associated with the longest telomere length and least telomere length attrition. Among over 2,000 participants from two distinct cohort studies, we found no pattern of alcohol consumption that was associated with longer telomere length or less telomere length attrition over time. Binge drinking may reduce telomere length. Using telomere length as a marker of age and health, these data fail to demonstrate any benefits of alcohol consumption, even when consumed in moderation.

{Alzheimer's disease progression and risk factors: A standardized comparison between six large data sets - Evans, S.; McRae-McKee, K.; Hadjichrysanthou, C.; Wong, M. M.; Ames, D.; Lopez, O.; de Wolf, F.; Anderson, R. M. (Alzheimers Dement (N Y), 2019)
There exist a large number of cohort studies that have been used to identify genetic and biological risk factors for developing Alzheimer's disease (AD). However, there is a disagreement between studies as to how strongly these risk factors affect the rate of progression through diagnostic groups toward AD. We have calculated the probability of transitioning through diagnostic groups in six studies and considered how uncertainty around the strength of the effect of these risk factors affects estimates of the distribution of individuals in each diagnostic group in an AD clinical trial simulator. In this work, we identify the optimal choice of widely collected variables for comparing data sets and calculating probabilities of progression toward AD. We use the estimated transition probabilities to inform stochastic simulations of AD progression that are based on a Markov model and compare predicted incidence rates to those in a community-based study, the Cardiovascular Health Study.

Assessment of the Relationship Between Genetic Determinants of Thyroid Function and Atrial Fibrillation: A Mendelian Randomization Study. - Ellervik, Christina; Roselli, Carolina; Christophersen, Ingrid E; Alonso, Alvaro; Pietzner, Maik; Sitlani, Collen M; Trompet, Stella; Arking, Dan E; Geelhoed, Bastiaan; Guo, Xiuqing; Kleber, Marcus E; Lin, Henry J; et al. (JAMA Cardiol, 2019)
Importance: Increased free thyroxine (FT4) and decreased thyrotropin are associated with increased risk of atrial fibrillation (AF) in observational studies, but direct involvement is unclear. Objective: To evaluate the potential direct involvement of thyroid traits on AF. Design, Setting, and Participants: Study-level mendelian randomization (MR) included 11 studies, and summary-level MR included 55 114 AF cases and 482 295 referents, all of European ancestry. Exposures: Genomewide significant variants were used as instruments for standardized FT4 and thyrotropin levels within the reference range, standardized triiodothyronine (FT3):FT4 ratio, hypothyroidism, standardized thyroid peroxidase antibody levels, and hyperthyroidism. Mendelian randomization used genetic risk scores in study-level analysis or individual single-nucleotide polymorphisms in 2-sample MR for the summary-level data. Main Outcomes and Measures: Prevalent and incident AF. Results: The study-level analysis included 7679 individuals with AF and 49 233 referents (mean age [standard error], 62 [3] years; 15 859 men [29.7%]). In study-level random-effects meta-analysis, the pooled hazard ratio of FT4 levels (nanograms per deciliter) for incident AF was 1.55 (95% CI, 1.09-2.20; P = .02; I2 = 76%) and the pooled odds ratio (OR) for prevalent AF was 2.80 (95% CI, 1.41-5.54; P = .003; I2 = 64%) in multivariable-adjusted analyses. The FT4 genetic risk score was associated with an increase in FT4 by 0.082 SD (standard error, 0.007; P < .001) but not with incident AF (risk ratio, 0.84; 95% CI, 0.62-1.14; P = .27) or prevalent AF (OR, 1.32; 95% CI, 0.64-2.73; P = .46). Similarly, in summary-level inverse-variance weighted random-effects MR, gene-based FT4 within the reference range was not associated with AF (OR, 1.01; 95% CI, 0.89-1.14; P = .88). However, gene-based increased FT3:FT4 ratio, increased thyrotropin within the reference range, and hypothyroidism were associated with AF with inverse-variance weighted random-effects OR of 1.33 (95% CI, 1.08-1.63; P = .006), 0.88 (95% CI, 0.84-0.92; P < .001), and 0.94 (95% CI, 0.90-0.99; P = .009), respectively, and robust to tests of horizontal pleiotropy. However, the subset of hypothyroidism single-nucleotide polymorphisms involved in autoimmunity and thyroid peroxidase antibodies levels were not associated with AF. Gene-based hyperthyroidism was associated with AF with MR-Egger OR of 1.31 (95% CI, 1.05-1.63; P = .02) with evidence of horizontal pleiotropy (P = .045). Conclusions and Relevance: Genetically increased FT3:FT4 ratio and hyperthyroidism, but not FT4 within the reference range, were associated with increased AF, and increased thyrotropin within the reference range and hypothyroidism were associated with decreased AF, supporting a pathway involving the pituitary-thyroid-cardiac axis.

The association between physical function and proximity to death in older adults: a multilevel analysis of 4,150 decedents from the Cardiovascular Health Study. - Karunananthan, Sathya; Moodie, Erica E M; Bergman, Howard; Payette, Hélène; Wolfson, David; Diehr, Paula H; Wolfson, Christina (Ann Epidemiol, 2019)
PURPOSE: When examining whether poor physical function is a risk factor for imminent death in older adults, one challenge is the lack of a meaningful time origin, a time point on which the estimate of time-to-death is anchored. In this study, we overcame this challenge by discarding the traditional-and flawed-approach of survival analysis with "time since beginning of follow up" as the time variable, and instead used a novel analytic approach that uses time-to-death as a covariate to examine its association with physical function. METHODS: Physical function and other covariates were measured annually in the Cardiovascular Health Study on 4150 individuals followed up to their time of death. Using multilevel models, we estimated gait speed and grip strength in relation to two time axes: age and proximity to death. RESULTS: As individuals approached death, both gait speed and grip strength decreased significantly. However, after adjustment for health and lifestyle covariates, there was significant variation in the level of physical function between individuals. CONCLUSION: Although physical function was significantly associated with time-to-death, there was significant variation in level of physical function between individuals at comparable proximity to death. A better understanding of these variations is needed before measures of physical function are recommended as a clinical tool for identifying individuals at high risk of death.

{Association of bone mineral density with hemoglobin and change in hemoglobin among older men and women: The Cardiovascular Health Study - Valderr?bano, R. J.; Buzkova, P.; Chang, P. Y.; Zakai, N. A.; Fink, H. A.; Robbins, J. A.; Lee, J. S.; Wu, J. Y. (Bone, 2019)
Osteoblasts and their precursors support hematopoiesis in the bone marrow. We hypothesized that declines in Hgb levels are associated with bone mineral density (BMD).\ The Cardiovascular Health Study is a prospective longitudinal study that enrolled 5888 community-dwelling adults aged >65 years and measured hemoglobin twice, in 1989-90 and 1992-93, as well as BMD by dual-energy X-ray absorptiometry (DXA) in 1994-95. In a subset of 1513 men and women with a Hgb in 1992-93 and BMD, we used linear regression to estimate associations of Hgb (per standard deviation (SD)) with total hip (TH), lumbar spine (LS) and total body (TB) BMD, and used Poisson regression to estimate associations of anemia (in 1992-93; Hgb <13 g/dL in men; <12 g/dL in women) with "low BMD" defined as T-score less than -1 at the TH. In 1277 participants with Hgb measured on average 2.9 years apart and BMD, we used linear regression to estimate the associations of annualized change in Hgb with TH, LS and TB BMD. All models included age, sex, study-site, race, smoking, alcohol use, weight, height, steroid use, physical activity score, self-reported health, previous cardiovascular disease and prior anti-fracture medication use.\ No significant association was observed between Hgb, measured a mean 2.2 years prior to BMD, and BMD at the TH and LS in men (TH beta = -0.60 [x 10-2 g/cm2per 1.1 g/dL Hgb], 95% CI: -1.88 to 0.68; LS beta = -1.69, 95% CI: -3.83 to 0.45) or women (TH beta = -0.49 [x 10-2 g/cm2per 1.3 g/dL Hgb], 95% CI: -1.57 to 0.59; LS beta = -0.40, 95% CI: -2.57 to 1.76). Anemia was not observed to be significantly associated with low BMD in men (RR = 0.99, 95% CI: 0.72-1.40) nor women (RR = 0.98, 95% CI: 0.82-1.17). The mean change in Hgb was a loss of 0.06 g/dL/year (SD = 0.32). Change in Hgb was not observed to be significantly associated with BMD in men (TH beta = -0.55[x 10-2 g/cm2per 1 g/dL annualized Hgb change], 95% CI: -4.28 to 3.19; LS beta = 0.63, 95% CI: -5.38 to 6.65) or women (TH beta = 0.92, 95% CI: -1.96 to 3.79; LS beta = -1.77, 95% CI: -7.52 to 3.98). No significant association was observed between anemia and low bone density by T-score in men and women.\ These findings support neither the hypothesis that low Hgb prior to bone density or decreases in Hgb are associated with bone density in older community-dwelling adults nor the use of Hgb level as a case-finding tool to prompt BMD measurement.

Associations of autozygosity with a broad range of human phenotypes. - Clark, David W; Okada, Yukinori; Moore, Kristjan H S; Mason, Dan; Pirastu, Nicola; Gandin, Ilaria; Mattsson, Hannele; Barnes, Catriona L K; Lin, Kuang; Zhao, Jing Hua; Deelen, Patrick; Rohde, Rebecca; et al. (Nat Commun, 2019)
In many species, the offspring of related parents suffer reduced reproductive success, a phenomenon known as inbreeding depression. In humans, the importance of this effect has remained unclear, partly because reproduction between close relatives is both rare and frequently associated with confounding social factors. Here, using genomic inbreeding coefficients (F) for >1.4 million individuals, we show that F is significantly associated (p < 0.0005) with apparently deleterious changes in 32 out of 100 traits analysed. These changes are associated with runs of homozygosity (ROH), but not with common variant homozygosity, suggesting that genetic variants associated with inbreeding depression are predominantly rare. The effect on fertility is striking: F equivalent to the offspring of first cousins is associated with a 55% decrease [95% CI 44-66%] in the odds of having children. Finally, the effects of F are confirmed within full-sibling pairs, where the variation in F is independent of all environmental confounding.

{Associations of circulating very-long-chain saturated fatty acids and incident type 2 diabetes: a pooled analysis of prospective cohort studies - Fretts, A. M.; Imamura, F.; Marklund, M.; Micha, R.; Wu, J. H. Y.; Murphy, R. A.; Chien, K. L.; McKnight, B.; Tintle, N.; Forouhi, N. G.; Qureshi, W. T.; Virtanen, J. K.; et al. (Am. J. Clin. Nutr., 2019)
Saturated fatty acids (SFAs) of different chain lengths have unique metabolic and biological effects, and a small number of recent studies suggest that higher circulating concentrations of the very-long-chain SFAs (VLSFAs) arachidic acid (20:0), behenic acid (22:0), and lignoceric acid (24:0) are associated with a lower risk of diabetes. Confirmation of these findings in a large and diverse population is needed.\ We investigated the associations of circulating VLSFAs 20:0, 22:0, and 24:0 with incident type 2 diabetes in prospective studies.\ Twelve studies that are part of the Fatty Acids and Outcomes Research Consortium participated in the analysis. Using Cox or logistic regression within studies and an inverse-variance-weighted meta-analysis across studies, we examined the associations of VLSFAs 20:0, 22:0, and 24:0 with incident diabetes among 51,431 participants.\ There were 14,276 cases of incident diabetes across participating studies. Higher circulating concentrations of 20:0, 22:0, and 24:0 were each associated with a lower risk of incident diabetes. Pooling across cohorts, the RR (95% CI) for incident diabetes comparing the 90th percentile to the 10th percentile was 0.78 (0.70, 0.87) for 20:0, 0.84 (0.77, 0.91) for 22:0, and 0.75 (0.69, 0.83) for 24:0 after adjustment for demographic, lifestyle, adiposity, and other health factors. Results were fully attenuated in exploratory models that adjusted for circulating 16:0 and triglycerides.\ Results from this pooled analysis indicate that higher concentrations of circulating VLSFAs 20:0, 22:0, and 24:0 are each associated with a lower risk of diabetes.

Associations of variants In the hexokinase 1 and interleukin 18 receptor regions with oxyhemoglobin saturation during sleep. - Cade, Brian E; Chen, Han; Stilp, Adrienne M; Louie, Tin; Ancoli-Israel, Sonia; Arens, Raanan; Barfield, Richard; Below, Jennifer E; Cai, Jianwen; Conomos, Matthew P; Evans, Daniel S; Frazier-Wood, Alexis C; et al. (PLoS Genet, 2019)
Sleep disordered breathing (SDB)-related overnight hypoxemia is associated with cardiometabolic disease and other comorbidities. Understanding the genetic bases for variations in nocturnal hypoxemia may help understand mechanisms influencing oxygenation and SDB-related mortality. We conducted genome-wide association tests across 10 cohorts and 4 populations to identify genetic variants associated with three correlated measures of overnight oxyhemoglobin saturation: average and minimum oxyhemoglobin saturation during sleep and the percent of sleep with oxyhemoglobin saturation under 90%. The discovery sample consisted of 8,326 individuals. Variants with p < 1 × 10(-6) were analyzed in a replication group of 14,410 individuals. We identified 3 significantly associated regions, including 2 regions in multi-ethnic analyses (2q12, 10q22). SNPs in the 2q12 region associated with minimum SpO2 (rs78136548 p = 2.70 × 10(-10)). SNPs at 10q22 were associated with all three traits including average SpO2 (rs72805692 p = 4.58 × 10(-8)). SNPs in both regions were associated in over 20,000 individuals and are supported by prior associations or functional evidence. Four additional significant regions were detected in secondary sex-stratified and combined discovery and replication analyses, including a region overlapping Reelin, a known marker of respiratory complex neurons.These are the first genome-wide significant findings reported for oxyhemoglobin saturation during sleep, a phenotype of high clinical interest. Our replicated associations with HK1 and IL18R1 suggest that variants in inflammatory pathways, such as the biologically-plausible NLRP3 inflammasome, may contribute to nocturnal hypoxemia.
Keywords: Adolescent; Adult; Aged; Aged, 80 and over; Cell Adhesion Molecules, Neuronal; Computational Biology; Extracellular Matrix Proteins; Female; Gene Regulatory Networks; Genetic Variation; Genome-Wide Association Study; Hexokinase; Humans; Hypoxia; Interleukin-18 Receptor alpha Subunit; Male; Middle Aged; Nerve Tissue Proteins; NLR Family, Pyrin Domain-Containing 3 Protein; Oxygen; Oxyhemoglobins; Polymorphism, Single Nucleotide; Quantitative Trait Loci; Serine Endopeptidases; Sleep; Sleep Apnea Syndromes; Young Adult

Biochemical markers of bone turnover and risk of incident hip fracture in older women: the Cardiovascular Health Study. - Massera, D; Xu, S; Walker, M D; Valderrábano, R J; Mukamal, K J; Ix, J H; Siscovick, D S; Tracy, R P; Robbins, J A; Biggs, M L; Xue, X; Kizer, J R (Osteoporos Int, 2019)
The relationships of osteocalcin (OC) and C-telopeptide of type I collagen (CTX) with long-term incidence of hip fracture were examined in 1680 post-menopausal women from a population-based study. CTX, but not OC, levels were associated with incident hip fracture in these participants, a relationship characterized by an inverted U-shape. INTRODUCTION: We sought to investigate the relationships of OC, a marker of bone formation, and CTX, a marker of bone resorption, with long-term incidence of hip fracture in older women. METHODS: We included 1680 women from the population-based Cardiovascular Health Study (mean [SD] age 74.5 [5.0] years). The longitudinal association of both markers with incidence of hip fracture was examined using multivariable Cox models. RESULTS: During a median follow-up of 12.3 years, 288 incident hip fractures occurred. Linear spline analysis did not demonstrate an association between OC levels and incident hip fracture. By contrast, increasing levels of CTX up to the middle-upper range were associated with a significantly greater risk of hip fracture (HR = 1.52 per SD increment, 95% CI = 1.10-2.09), while further increases were associated with a marginally non-significant lower risk (HR = 0.80 per SD increment, 95% CI = 0.63-1.01), after full adjustment for potential confounders. In analyses of quartiles, CTX exhibited a similar inverted U-shaped relationship with incident fracture after adjustment, with a significant association observed only for the comparison of quartile 3 to quartile 1 (HR = 1.63, 95% CI = 1.10-2.43). In a subset with available measures, both OC and CTX were inversely associated with bone mineral density of the hip. CONCLUSION: CTX, but not OC, levels were associated with incident hip fracture in post-menopausal women, a relationship characterized by an inverted U-shape. These findings highlight the complex relationship of bone turnover markers with hip fracture risk.

Biomarkers of Dietary Omega-6 Fatty Acids and Incident Cardiovascular Disease and Mortality. - Marklund, Matti; Wu, Jason H Y; Imamura, Fumiaki; Del Gobbo, Liana C; Fretts, Amanda; de Goede, Janette; Shi, Peilin; Tintle, Nathan; Wennberg, Maria; Aslibekyan, Stella; Chen, Tzu-An; de Oliveira Otto, Marcia C; et al. (Circulation, 2019)
BACKGROUND: Global dietary recommendations for and cardiovascular effects of linoleic acid, the major dietary omega-6 fatty acid, and its major metabolite, arachidonic acid, remain controversial. To address this uncertainty and inform international recommendations, we evaluated how in vivo circulating and tissue levels of linoleic acid (LA) and arachidonic acid (AA) relate to incident cardiovascular disease (CVD) across multiple international studies. METHODS: We performed harmonized, de novo, individual-level analyses in a global consortium of 30 prospective observational studies from 13 countries. Multivariable-adjusted associations of circulating and adipose tissue LA and AA biomarkers with incident total CVD and subtypes (coronary heart disease, ischemic stroke, cardiovascular mortality) were investigated according to a prespecified analytic plan. Levels of LA and AA, measured as the percentage of total fatty acids, were evaluated linearly according to their interquintile range (ie, the range between the midpoint of the first and fifth quintiles), and categorically by quintiles. Study-specific results were pooled using inverse-variance-weighted meta-analysis. Heterogeneity was explored by age, sex, race, diabetes mellitus, statin use, aspirin use, omega-3 levels, and fatty acid desaturase 1 genotype (when available). RESULTS: In 30 prospective studies with medians of follow-up ranging 2.5 to 31.9 years, 15 198 incident cardiovascular events occurred among 68 659 participants. Higher levels of LA were significantly associated with lower risks of total CVD, cardiovascular mortality, and ischemic stroke, with hazard ratios per interquintile range of 0.93 (95% CI, 0.88-0.99), 0.78 (0.70-0.85), and 0.88 (0.79-0.98), respectively, and nonsignificantly with lower coronary heart disease risk (0.94; 0.88-1.00). Relationships were similar for LA evaluated across quintiles. AA levels were not associated with higher risk of cardiovascular outcomes; in a comparison of extreme quintiles, higher levels were associated with lower risk of total CVD (0.92; 0.86-0.99). No consistent heterogeneity by population subgroups was identified in the observed relationships. CONCLUSIONS: In pooled global analyses, higher in vivo circulating and tissue levels of LA and possibly AA were associated with lower risk of major cardiovascular events. These results support a favorable role for LA in CVD prevention.

Blood Leukocyte DNA Methylation Predicts Risk of Future Myocardial Infarction and Coronary Heart Disease. - Agha, Golareh; Mendelson, Michael M; Ward-Caviness, Cavin K; Joehanes, Roby; Huan, Tianxiao; Gondalia, Rahul; Salfati, Elias; Brody, Jennifer A; Fiorito, Giovanni; Bressler, Jan; Chen, Brian H; Ligthart, Symen; et al. (Circulation, 2019)
BACKGROUND: DNA methylation is implicated in coronary heart disease (CHD), but current evidence is based on small, cross-sectional studies. We examined blood DNA methylation in relation to incident CHD across multiple prospective cohorts. METHODS: Nine population-based cohorts from the United States and Europe profiled epigenome-wide blood leukocyte DNA methylation using the Illumina Infinium 450k microarray, and prospectively ascertained CHD events including coronary insufficiency/unstable angina, recognized myocardial infarction, coronary revascularization, and coronary death. Cohorts conducted race-specific analyses adjusted for age, sex, smoking, education, body mass index, blood cell type proportions, and technical variables. We conducted fixed-effect meta-analyses across cohorts. RESULTS: Among 11 461 individuals (mean age 64 years, 67% women, 35% African American) free of CHD at baseline, 1895 developed CHD during a mean follow-up of 11.2 years. Methylation levels at 52 CpG (cytosine-phosphate-guanine) sites were associated with incident CHD or myocardial infarction (false discovery rate<0.05). These CpGs map to genes with key roles in calcium regulation (ATP2B2, CASR, GUCA1B, HPCAL1), and genes identified in genome- and epigenome-wide studies of serum calcium (CASR), serum calcium-related risk of CHD (CASR), coronary artery calcified plaque (PTPRN2), and kidney function (CDH23, HPCAL1), among others. Mendelian randomization analyses supported a causal effect of DNA methylation on incident CHD; these CpGs map to active regulatory regions proximal to long non-coding RNA transcripts. CONCLUSION: Methylation of blood-derived DNA is associated with risk of future CHD across diverse populations and may serve as an informative tool for gaining further insight on the development of CHD.
Keywords: Adult; Aged; Cohort Studies; Coronary Disease; CpG Islands; DNA Methylation; Europe; Female; Genome-Wide Association Study; Humans; Incidence; Leukocytes; Male; Middle Aged; Myocardial Infarction; Population Groups; Prognosis; Prospective Studies; Risk; United States

A catalog of genetic loci associated with kidney function from analyses of a million individuals. - Wuttke, Matthias; Li, Yong; Li, Man; Sieber, Karsten B; Feitosa, Mary F; Gorski, Mathias; Tin, Adrienne; Wang, Lihua; Chu, Audrey Y; Hoppmann, Anselm; Kirsten, Holger; Giri, Ayush; et al. (Nat Genet, 2019)
Chronic kidney disease (CKD) is responsible for a public health burden with multi-systemic complications. Through trans-ancestry meta-analysis of genome-wide association studies of estimated glomerular filtration rate (eGFR) and independent replication (n = 1,046,070), we identified 264 associated loci (166 new). Of these, 147 were likely to be relevant for kidney function on the basis of associations with the alternative kidney function marker blood urea nitrogen (n = 416,178). Pathway and enrichment analyses, including mouse models with renal phenotypes, support the kidney as the main target organ. A genetic risk score for lower eGFR was associated with clinically diagnosed CKD in 452,264 independent individuals. Colocalization analyses of associations with eGFR among 783,978 European-ancestry individuals and gene expression across 46 human tissues, including tubulo-interstitial and glomerular kidney compartments, identified 17 genes differentially expressed in kidney. Fine-mapping highlighted missense driver variants in 11 genes and kidney-specific regulatory variants. These results provide a comprehensive priority list of molecular targets for translational research.
Keywords: Chromosome Mapping; European Continental Ancestry Group; Genetic Association Studies; Genetic Predisposition to Disease; Genome-Wide Association Study; Glomerular Filtration Rate; Humans; Inheritance Patterns; Kidney Function Tests; Phenotype; Polymorphism, Single Nucleotide; Quantitative Trait Loci; Quantitative Trait, Heritable; Renal Insufficiency, Chronic; Uromodulin

Common Genetic Variation in Relation to Brachial Vascular Dimensions and Flow-Mediated Vasodilation. - Dörr, Marcus; Hamburg, Naomi M; Müller, Christian; Smith, Nicholas L; Gustafsson, Stefan; Lehtimäki, Terho; Teumer, Alexander; Zeller, Tanja; Li, Xiaohui; Lind, Lars; Raitakari, Olli T; Völker, Uwe; et al. (Circ Genom Precis Med, 2019)

Discrepancy in Frailty Identification: Move beyond Predictive Validity. - Xue, Qian-Li; Tian, Jing; Walston, Jeremy D; Chaves, Paulo H M; Newman, Anne B; Bandeen-Roche, Karen (J Gerontol A Biol Sci Med Sci, 2019)
BACKGROUND: To evaluate the discordance in frailty classification between the frailty index (FI) and the physical frailty phenotype (PFP) and identify factors discriminating those with discordant frailty classification from each other and from those for whom the assessments agree. METHODS: A prospective observational study of older adults aged 65 and older selected from Medicare eligibility lists in four US communities (n=5,362). The PFP was measured by the Cardiovascular Health Study PFP. Subjects meeting ≥3 of the 5 criteria were deemed frail. The FI was calculated as the proportion of deficits in an a priori selected set of 48 measures and subjects were classified as frail if FI>0.35. RESULTS: The prevalence of frailty was 7.0% by the PFP and 8.3% by the FI. Of the 730 deemed frail by either instrument, only 12% were in agreement; whereas 39% were classified as frail by PFP but not FI; and 48% were classified as frail by FI but not PFP. Participants aged 65-72 or greater disease burden were mostly likely to be characterized as being FI-frail but not PFP-frail. The associations of frailty with age and mortality was stronger when frailty was measured by the PFP rather than the FI. CONCLUSIONS: Despite comparable frailty prevalence between the PFP and the FI, there was substantial discordance in individual-level classification, with highest agreement existing only in the most vulnerable subset. These findings suggest that there are clinically important contexts in which PFP and FI cannot be used interchangeably.

Discriminative Accuracy of FEV1:FVC Thresholds for COPD-Related Hospitalization and Mortality. - Bhatt, Surya P; Balte, Pallavi P; Schwartz, Joseph E; Cassano, Patricia A; Couper, David; Jacobs, David R; Kalhan, Ravi; O'Connor, George T; Yende, Sachin; Sanders, Jason L; Umans, Jason G; Dransfield, Mark T; et al. (JAMA, 2019)
Importance: According to numerous current guidelines, the diagnosis of chronic obstructive pulmonary disease (COPD) requires a ratio of the forced expiratory volume in the first second to the forced vital capacity (FEV1:FVC) of less than 0.70, yet this fixed threshold is based on expert opinion and remains controversial. Objective: To determine the discriminative accuracy of various FEV1:FVC fixed thresholds for predicting COPD-related hospitalization and mortality. Design, Setting, and Participants: The National Heart, Lung, and Blood Institute (NHLBI) Pooled Cohorts Study harmonized and pooled data from 4 US general population-based cohorts (Atherosclerosis Risk in Communities Study; Cardiovascular Health Study; Health, Aging, and Body Composition Study; and Multi-Ethnic Study of Atherosclerosis). Participants aged 45 to 102 years were enrolled from 1987 to 2000 and received follow-up longitudinally through 2016. Exposures: Presence of airflow obstruction, which was defined by a baseline FEV1:FVC less than a range of fixed thresholds (0.75 to 0.65) or less than the lower limit of normal as defined by Global Lung Initiative reference equations (LLN). Main Outcomes and Measures: The primary outcome was a composite of COPD hospitalization and COPD-related mortality, defined by adjudication or administrative criteria. The optimal fixed FEV1:FVC threshold was defined by the best discrimination for these COPD-related events as indexed using the Harrell C statistic from unadjusted Cox proportional hazards models. Differences in C statistics were compared with respect to less than 0.70 and less than LLN thresholds using a nonparametric approach. Results: Among 24 207 adults in the pooled cohort (mean [SD] age at enrollment, 63 [10.5] years; 12 990 [54%] women; 16 794 [69%] non-Hispanic white; 15 181 [63%] ever smokers), complete follow-up was available for 11 077 (77%) at 15 years. During a median follow-up of 15 years, 3925 participants experienced COPD-related events over 340 757 person-years of follow-up (incidence density rate, 11.5 per 1000 person-years), including 3563 COPD-related hospitalizations and 447 COPD-related deaths. With respect to discrimination of COPD-related events, the optimal fixed threshold (0.71; C statistic for optimal fixed threshold, 0.696) was not significantly different from the 0.70 threshold (difference, 0.001 [95% CI, -0.002 to 0.004]) but was more accurate than the LLN threshold (difference, 0.034 [95% CI, 0.028 to 0.041]). The 0.70 threshold provided optimal discrimination in the subgroup analysis of ever smokers and in adjusted models. Conclusions and Relevance: Defining airflow obstruction as FEV1:FVC less than 0.70 provided discrimination of COPD-related hospitalization and mortality that was not significantly different or was more accurate than other fixed thresholds and the LLN. These results support the use of FEV1:FVC less than 0.70 to identify individuals at risk of clinically significant COPD.
Keywords: Aged; Aged, 80 and over; Cohort Studies; Female; Forced Expiratory Volume; Hospitalization; Humans; Male; Middle Aged; Prognosis; Proportional Hazards Models; Pulmonary Disease, Chronic Obstructive; Risk Assessment; Vital Capacity

Disentangling the genetics of lean mass. - Karasik, David; Zillikens, M Carola; Hsu, Yi-Hsiang; Aghdassi, Ali; Åkesson, Kristina; Amin, Najaf; Barroso, Inês; Bennett, David A; Bertram, Lars; Bochud, Murielle; Borecki, Ingrid B; Broer, Linda; et al. (Am J Clin Nutr, 2019)
Background: Lean body mass (LM) plays an important role in mobility and metabolic function. We previously identified five loci associated with LM adjusted for fat mass in kilograms. Such an adjustment may reduce the power to identify genetic signals having an association with both lean mass and fat mass. Objectives: To determine the impact of different fat mass adjustments on genetic architecture of LM and identify additional LM loci. Methods: We performed genome-wide association analyses for whole-body LM (20 cohorts of European ancestry with n = 38,292) measured using dual-energy X-ray absorptiometry) or bioelectrical impedance analysis, adjusted for sex, age, age2, and height with or without fat mass adjustments (Model 1 no fat adjustment; Model 2 adjustment for fat mass as a percentage of body mass; Model 3 adjustment for fat mass in kilograms). Results: Seven single-nucleotide polymorphisms (SNPs) in separate loci, including one novel LM locus (TNRC6B), were successfully replicated in an additional 47,227 individuals from 29 cohorts. Based on the strengths of the associations in Model 1 vs Model 3, we divided the LM loci into those with an effect on both lean mass and fat mass in the same direction and refer to those as "sumo wrestler" loci (FTO and MC4R). In contrast, loci with an impact specifically on LM were termed "body builder" loci (VCAN and ADAMTSL3). Using existing available genome-wide association study databases, LM increasing alleles of SNPs in sumo wrestler loci were associated with an adverse metabolic profile, whereas LM increasing alleles of SNPs in "body builder" loci were associated with metabolic protection. Conclusions: In conclusion, we identified one novel LM locus (TNRC6B). Our results suggest that a genetically determined increase in lean mass might exert either harmful or protective effects on metabolic traits, depending on its relation to fat mass.

Epigenome-wide association analysis of daytime sleepiness in the Multi-Ethnic Study of Atherosclerosis reveals African-American-specific associations. - Barfield, Richard; Wang, Heming; Liu, Yongmei; Brody, Jennifer A; Swenson, Brenton; Li, Ruitong; Bartz, Traci M; Sotoodehnia, Nona; Chen, Yii-der I; Cade, Brian E; Chen, Han; Patel, Sanjay R; et al. (Sleep, 2019)
STUDY OBJECTIVES: Daytime sleepiness is a consequence of inadequate sleep, sleep-wake control disorder, or other medical conditions. Population variability in prevalence of daytime sleepiness is likely due to genetic and biological factors as well as social and environmental influences. DNA methylation (DNAm) potentially influences multiple health outcomes. Here, we explored the association between DNAm and daytime sleepiness quantified by the Epworth Sleepiness Scale (ESS). METHODS: We performed multi-ethnic and ethnic-specific epigenome-wide association studies for DNAm and ESS in the Multi-Ethnic Study of Atherosclerosis (MESA; n = 619) and the Cardiovascular Health Study (n = 483), with cross-study replication and meta-analysis. Genetic variants near ESS-associated DNAm were analyzed for methylation quantitative trait loci and followed with replication of genotype-sleepiness associations in the UK Biobank. RESULTS: In MESA only, we detected four DNAm-ESS associations: one across all race/ethnic groups; three in African-Americans (AA) only. Two of the MESA AA associations, in genes KCTD5 and RXRA, nominally replicated in CHS (p-value < 0.05). In the AA meta-analysis, we detected 14 DNAm-ESS associations (FDR q-value < 0.05, top association p-value = 4.26 × 10-8). Three DNAm sites mapped to genes (CPLX3, GFAP, and C7orf50) with biological relevance. We also found evidence for associations with DNAm sites in RAI1, a gene associated with sleep and circadian phenotypes. UK Biobank follow-up analyses detected SNPs in RAI1, RXRA, and CPLX3 with nominal sleepiness associations. CONCLUSIONS: We identified methylation sites in multiple genes possibly implicated in daytime sleepiness. Most significant DNAm-ESS associations were specific to AA. Future work is needed to identify mechanisms driving ancestry-specific methylation effects.

{Equalization of four cardiovascular risk algorithms after systematic recalibration: individual-participant meta-analysis of 86 prospective studies - Pennells, L.; Kaptoge, S.; Wood, A.; Sweeting, M.; Zhao, X.; White, I.; Burgess, S.; Willeit, P.; Bolton, T.; Moons, K. G. M.; van der Schouw, Y. T.; Selmer, R.; et al. (Eur Heart J, 2019)
There is debate about the optimum algorithm for cardiovascular disease (CVD) risk estimation. We conducted head-to-head comparisons of four algorithms recommended by primary prevention guidelines, before and after 'recalibration', a method that adapts risk algorithms to take account of differences in the risk characteristics of the populations being studied.\ Using individual-participant data on 360 737 participants without CVD at baseline in 86 prospective studies from 22 countries, we compared the Framingham risk score (FRS), Systematic COronary Risk Evaluation (SCORE), pooled cohort equations (PCE), and Reynolds risk score (RRS). We calculated measures of risk discrimination and calibration, and modelled clinical implications of initiating statin therapy in people judged to be at 'high' 10 year CVD risk. Original risk algorithms were recalibrated using the risk factor profile and CVD incidence of target populations. The four algorithms had similar risk discrimination. Before recalibration, FRS, SCORE, and PCE over-predicted CVD risk on average by 10%, 52%, and 41%, respectively, whereas RRS under-predicted by 10%. Original versions of algorithms classified 29-39% of individuals aged â‰¥40 years as high risk. By contrast, recalibration reduced this proportion to 22-24% for every algorithm. We estimated that to prevent one CVD event, it would be necessary to initiate statin therapy in 44-51 such individuals using original algorithms, in contrast to 37-39 individuals with recalibrated algorithms.\ Before recalibration, the clinical performance of four widely used CVD risk algorithms varied substantially. By contrast, simple recalibration nearly equalized their performance and improved modelled targeting of preventive action to clinical need.

{Exome sequencing of 20,791 cases of type 2 diabetes and 24,440 controls - Flannick, J.; Mercader, J. M.; Fuchsberger, C.; Udler, M. S.; Mahajan, A.; Wessel, J.; Teslovich, T. M.; Caulkins, L.; Koesterer, R.; Barajas-Olmos, F.; Blackwell, T. W.; Boerwinkle, E.; et al. (Nature, 2019)
Protein-coding genetic variants that strongly affect disease risk can yield relevant clues to disease pathogenesis. Here we report exome-sequencing analyses of 20,791 individuals with type 2 diabetes (T2D) and 24,440 non-diabetic control participants from 5 ancestries. We identify gene-level associations of rare variants (with minor allele frequencies of less than 0.5%) in 4 genes at exome-wide significance, including a series of more than 30 SLC30A8 alleles that conveys protection against T2D, and in 12 gene sets, including those corresponding to T2D drug targets (P = 6.1 Ã— 10-3) and candidate genes from knockout mice (P = 5.2 Ã— 10-3). Within our study, the strongest T2D gene-level signals for rare variants explain at most 25% of the heritability of the strongest common single-variant signals, and the gene-level effect sizes of the rare variants that we observed in established T2D drug targets will require 75,000-185,000 sequenced cases to achieve exome-wide significance. We propose a method to interpret these modest rare-variant associations and to incorporate these associations into future target or gene prioritization efforts.

{Exome-Derived Adiponectin-Associated Variants Implicate Obesity and Lipid Biology - Spracklen, C. N.; Karaderi, T.; Yaghootkar, H.; Schurmann, C.; Fine, R. S.; Kutalik, Z.; Preuss, M. H.; Lu, Y.; Wittemans, L. B. L.; Adair, L. S.; Allison, M.; Amin, N.; et al. (Am J Hum Genet, 2019)

{Exome-Derived Adiponectin-Associated Variants Implicate Obesity and Lipid Biology - Spracklen, C. N.; Karaderi, T.; Yaghootkar, H.; Schurmann, C.; Fine, R. S.; Kutalik, Z.; Preuss, M. H.; Lu, Y.; Wittemans, L. B. L.; Adair, L. S.; Allison, M.; Amin, N.; et al. (Am J Hum Genet, 2019)
) with at least one obesity or lipid trait. Candidate genes include PRKAR2A, PTH1R, and HDAC9, which have been suggested to play roles in adipocyte differentiation or bone marrow adipose tissue. Taken together, these findings provide further insights into the processes that influence circulating adiponectin levels.

Genetic architecture of subcortical brain structures in 38,851 individuals. - Satizabal, Claudia L; Adams, Hieab H H; Hibar, Derrek P; White, Charles C; Knol, Maria J; Stein, Jason L; Scholz, Markus; Sargurupremraj, Muralidharan; Jahanshad, Neda; Roshchupkin, Gennady V; Smith, Albert V; Bis, Joshua C; et al. (Nat Genet, 2019)
Subcortical brain structures are integral to motion, consciousness, emotions and learning. We identified common genetic variation related to the volumes of the nucleus accumbens, amygdala, brainstem, caudate nucleus, globus pallidus, putamen and thalamus, using genome-wide association analyses in almost 40,000 individuals from CHARGE, ENIGMA and UK Biobank. We show that variability in subcortical volumes is heritable, and identify 48 significantly associated loci (40 novel at the time of analysis). Annotation of these loci by utilizing gene expression, methylation and neuropathological data identified 199 genes putatively implicated in neurodevelopment, synaptic signaling, axonal transport, apoptosis, inflammation/infection and susceptibility to neurological disorders. This set of genes is significantly enriched for Drosophila orthologs associated with neurodevelopmental phenotypes, suggesting evolutionarily conserved mechanisms. Our findings uncover novel biology and potential drug targets underlying brain development and disease.

Genetic meta-analysis of diagnosed Alzheimer's disease identifies new risk loci and implicates Aβ, tau, immunity and lipid processing. - Kunkle, Brian W; Grenier-Boley, Benjamin; Sims, Rebecca; Bis, Joshua C; Damotte, Vincent; Naj, Adam C; Boland, Anne; Vronskaya, Maria; van der Lee, Sven J; Amlie-Wolf, Alexandre; Bellenguez, Céline; Frizatti, Aura; et al. (Nat Genet, 2019)
Risk for late-onset Alzheimer's disease (LOAD), the most prevalent dementia, is partially driven by genetics. To identify LOAD risk loci, we performed a large genome-wide association meta-analysis of clinically diagnosed LOAD (94,437 individuals). We confirm 20 previous LOAD risk loci and identify five new genome-wide loci (IQCK, ACE, ADAM10, ADAMTS1, and WWOX), two of which (ADAM10, ACE) were identified in a recent genome-wide association (GWAS)-by-familial-proxy of Alzheimer's or dementia. Fine-mapping of the human leukocyte antigen (HLA) region confirms the neurological and immune-mediated disease haplotype HLA-DR15 as a risk factor for LOAD. Pathway analysis implicates immunity, lipid metabolism, tau binding proteins, and amyloid precursor protein (APP) metabolism, showing that genetic variants affecting APP and Aβ processing are associated not only with early-onset autosomal dominant Alzheimer's disease but also with LOAD. Analyses of risk genes and pathways show enrichment for rare variants (P = 1.32 × 10), indicating that additional rare variants remain to be identified. We also identify important genetic correlations between LOAD and traits such as family history of dementia and education.

{Genome-wide association meta-analyses and fine-mapping elucidate pathways influencing albuminuria - Teumer, A.; Li, Y.; Ghasemi, S.; Prins, B. P.; Wuttke, M.; Hermle, T.; Giri, A.; Sieber, K. B.; Qiu, C.; Kirsten, H.; Tin, A.; Chu, A. Y.; et al. (Nat Commun, 2019)
Increased levels of the urinary albumin-to-creatinine ratio (UACR) are associated with higher risk of kidney disease progression and cardiovascular events, but underlying mechanisms are incompletely understood. Here, we conduct trans-ethnic (n = 564,257) and European-ancestry specific meta-analyses of genome-wide association studies of UACR, including ancestry- and diabetes-specific analyses, and identify 68 UACR-associated loci. Genetic correlation analyses and risk score associations in an independent electronic medical records database (n = 192,868) reveal connections with proteinuria, hyperlipidemia, gout, and hypertension. Fine-mapping and trans-Omics analyses with gene expression in 47 tissues and plasma protein levels implicate genes potentially operating through differential expression in kidney (including TGFB1, MUC1, PRKCI, and OAF), and allow coupling of UACR associations to altered plasma OAF concentrations. Knockdown of OAF and PRKCI orthologs in Drosophila nephrocytes reduces albumin endocytosis. Silencing fly PRKCI further impairs slit diaphragm formation. These results generate a priority list of genes and pathways for translational research to reduce albuminuria.

{A genome-wide association study identifies genetic loci associated with specific lobar brain volumes - van der Lee, S. J.; Knol, M. J.; Chauhan, G.; Satizabal, C. L.; Smith, A. V.; Hofer, E.; Bis, J. C.; Hibar, D. P.; Hilal, S.; van den Akker, E. B.; Arfanakis, K.; Bernard, M.; et al. (Commun Biol, 2019)
Brain lobar volumes are heritable but genetic studies are limited. We performed genome-wide association studies of frontal, occipital, parietal and temporal lobe volumes in 16,016 individuals, and replicated our findings in 8,789 individuals. We identified six genetic loci associated with specific lobar volumes independent of intracranial volume. Two loci, associated with occipital (6q22.32) and temporal lobe volume (12q14.3), were previously reported to associate with intracranial and hippocampal volume, respectively. We identified four loci previously unknown to affect brain volumes: 3q24 for parietal lobe volume, and 1q22, 4p16.3 and 14q23.1 for occipital lobe volume. The associated variants were located in regions enriched for histone modifications (DAAM1 and THBS3), or close to genes causing Mendelian brain-related diseases (ZIC4 and FGFRL1). No genetic overlap between lobar volumes and neurological or psychiatric diseases was observed. Our findings reveal part of the complex genetics underlying brain development and suggest a role for regulatory regions in determining brain volumes.

A genome-wide association study identifies new loci for factor VII and implicates factor VII in ischemic stroke etiology. - de Vries, Paul S; Sabater-Lleal, Maria; Huffman, Jennifer E; Marten, Jonathan; Song, Ci; Pankratz, Nathan; Bartz, Traci M; de Haan, Hugoline G; Delgado, Graciela E; Eicher, John D; Martinez-Perez, Angel; Ward-Caviness, Cavin K; et al. (Blood, 2019)
Factor VII (FVII) is an important component of the coagulation cascade. Few genetic loci regulating FVII activity and/or levels have been discovered to date. We conducted a meta-analysis of 9 genome-wide association studies of plasma FVII levels (7 FVII activity and 2 FVII antigen) among 27 495 participants of European and African ancestry. Each study performed ancestry-specific association analyses. Inverse variance weighted meta-analysis was performed within each ancestry group and then combined for a -ancestry meta-analysis. Our primary analysis included the 7 studies that measured FVII activity, and a secondary analysis included all 9 studies. We provided functional genomic validation for newly identified significant loci by silencing candidate genes in a human liver cell line (HuH7) using small-interfering RNA and then measuring messenger RNA and FVII protein expression. Lastly, we used meta-analysis results to perform Mendelian randomization analysis to estimate the causal effect of FVII activity on coronary artery disease, ischemic stroke (IS), and venous thromboembolism. We identified 2 novel ( and ) and 6 known loci associated with FVII activity, explaining 19.0% of the phenotypic variance. Adding FVII antigen data to the meta-analysis did not result in the discovery of further loci. Silencing in HuH7 cells upregulated FVII, whereas silencing downregulated FVII. Mendelian randomization analyses suggest that FVII activity has a positive causal effect on the risk of IS. Variants at and contribute to FVII activity by regulating expression levels. FVII activity appears to contribute to the etiology of IS in the general population.

{Genome-Wide Association Study of Apparent Treatment-Resistant Hypertension in the CHARGE Consortium: The CHARGE Pharmacogenetics Working Group - Irvin, M. R.; Sitlani, C. M.; Floyd, J. S.; Psaty, B. M.; Bis, J. C.; Wiggins, K. L.; Whitsel, E. A.; Sturmer, T.; Stewart, J.; Raffield, L.; Sun, F.; Liu, C. T.; et al. (Am J Hypertens, 2019)
{Only a handful of genetic discovery efforts in apparent treatment-resistant hypertension (aTRH) have been described.\ We conducted a case-control genome-wide association study of aTRH among persons treated for hypertension, using data from 10 cohorts of European ancestry (EA) and 5 cohorts of African ancestry (AA). Cases were treated with 3 different antihypertensive medication classes and had blood pressure (BP) above goal (systolic BP â‰¥ 140 mm Hg and/or diastolic BP â‰¥ 90 mm Hg) or 4 or more medication classes regardless of BP control (nEA = 931

Genome-Wide Association Study of Apparent Treatment-Resistant Hypertension in the CHARGE Consortium: The CHARGE Pharmacogenetics Working Group. - Irvin, Marguerite R; Sitlani, Colleen M; Floyd, James S; Psaty, Bruce M; Bis, Joshua C; Wiggins, Kerri L; Whitsel, Eric A; Stürmer, Til; Stewart, James; Raffield, Laura; Sun, Fangui; Liu, Ching-Ti; et al. (Am J Hypertens, 2019)
BACKGROUND: Only a handful of genetic discovery efforts in apparent treatment-resistant hypertension (aTRH) have been described. METHODS: We conducted a case-control genome-wide association study of aTRH among persons treated for hypertension, using data from 10 cohorts of European ancestry (EA) and 5 cohorts of African ancestry (AA). Cases were treated with 3 different antihypertensive medication classes and had blood pressure (BP) above goal (systolic BP ≥ 140 mm Hg and/or diastolic BP ≥ 90 mm Hg) or 4 or more medication classes regardless of BP control (nEA = 931, nAA = 228). Both a normotensive control group and a treatment-responsive control group were considered in separate analyses. Normotensive controls were untreated (nEA = 14,210, nAA = 2,480) and had systolic BP/diastolic BP < 140/90 mm Hg. Treatment-responsive controls (nEA = 5,266, nAA = 1,817) had BP at goal (<140/90 mm Hg), while treated with one antihypertensive medication class. Individual cohorts used logistic regression with adjustment for age, sex, study site, and principal components for ancestry to examine the association of single-nucleotide polymorphisms with case-control status. Inverse variance-weighted fixed-effects meta-analyses were carried out using METAL. RESULTS: The known hypertension locus, CASZ1, was a top finding among EAs (P = 1.1 × 10-8) and in the race-combined analysis (P = 1.5 × 10-9) using the normotensive control group (rs12046278, odds ratio = 0.71 (95% confidence interval: 0.6-0.8)). Single-nucleotide polymorphisms in this locus were robustly replicated in the Million Veterans Program (MVP) study in consideration of a treatment-responsive control group. There were no statistically significant findings for the discovery analyses including treatment-responsive controls. CONCLUSION: This genomic discovery effort for aTRH identified CASZ1 as an aTRH risk locus.
Keywords: Aged; Antihypertensive Agents; Black or African American; Blood Pressure; Case-Control Studies; DNA (Cytosine-5-)-Methyltransferases; DNA Methyltransferase 3A; DNA-Binding Proteins; Drug Resistance; Dystrophin-Associated Proteins; Europe; Female; Genetic Loci; Genome-Wide Association Study; Humans; Hypertension; Male; Middle Aged; Myosin Heavy Chains; Myosin Type V; Neuropeptides; Pharmacogenetics; Pharmacogenomic Variants; Polymorphism, Single Nucleotide; Risk Assessment; Risk Factors; Transcription Factors; United States; White People

{Genome-Wide Association Transethnic Meta-Analyses Identifies Novel Associations Regulating Coagulation Factor VIII and von Willebrand Factor Plasma Levels - Sabater-Lleal, M.; Huffman, J. E.; de Vries, P. S.; Marten, J.; Mastrangelo, M. A.; Song, C.; Pankratz, N.; Ward-Caviness, C. K.; Yanek, L. R.; Trompet, S.; Delgado, G. E.; Guo, X.; et al. (Circulation, 2019)
Factor VIII (FVIII) and its carrier protein von Willebrand factor (VWF) are associated with risk of arterial and venous thrombosis and with hemorrhagic disorders. We aimed to identify and functionally test novel genetic associations regulating plasma FVIII and VWF.\ We meta-analyzed genome-wide association results from 46 354 individuals of European, African, East Asian, and Hispanic ancestry. All studies performed linear regression analysis using an additive genetic model and associated ≈35 million imputed variants with natural log-transformed phenotype levels. In vitro gene silencing in cultured endothelial cells was performed for candidate genes to provide additional evidence on association and function. Two-sample Mendelian randomization analyses were applied to test the causal role of FVIII and VWF plasma levels on the risk of arterial and venous thrombotic events.\ We identified 13 novel genome-wide significant ( P≤2.5×10-8) associations, 7 with FVIII levels ( FCHO2/TMEM171/TNPO1, HLA, SOX17/RP1, LINC00583/NFIB, RAB5C-KAT2A, RPL3/TAB1/SYNGR1, and ARSA) and 11 with VWF levels ( PDHB/PXK/KCTD6, SLC39A8, FCHO2/TMEM171/TNPO1, HLA, GIMAP7/GIMAP4, OR13C5/NIPSNAP, DAB2IP, C2CD4B, RAB5C-KAT2A, TAB1/SYNGR1, and ARSA), beyond 10 previously reported associations with these phenotypes. Functional validation provided further evidence of association for all loci on VWF except ARSA and DAB2IP. Mendelian randomization suggested causal effects of plasma FVIII activity levels on venous thrombosis and coronary artery disease risk and plasma VWF levels on ischemic stroke risk.\ The meta-analysis identified 13 novel genetic loci regulating FVIII and VWF plasma levels, 10 of which we validated functionally. We provide some evidence for a causal role of these proteins in thrombotic events.

Genome-wide meta-analysis of SNP and antihypertensive medication interactions on left ventricular traits in African Americans. - Do, Anh N; Zhao, Wei; Baldridge, Abigail S; Raffield, Laura M; Wiggins, Kerri L; Shah, Sanjiv J; Aslibekyan, Stella; Tiwari, Hemant K; Limdi, Nita; Zhi, Degui; Sitlani, Colleen M; Taylor, Kent D; et al. (Mol Genet Genomic Med, 2019)
BACKGROUND: Left ventricular (LV) hypertrophy affects up to 43% of African Americans (AAs). Antihypertensive treatment reduces LV mass (LVM). However, interindividual variation in LV traits in response to antihypertensive treatments exists. We hypothesized that genetic variants may modify the association of antihypertensive treatment class with LV traits measured by echocardiography. METHODS: We evaluated the main effects of the three most common antihypertensive treatments for AAs as well as the single nucleotide polymorphism (SNP)-by-drug interaction on LVM and relative wall thickness (RWT) in 2,068 participants across five community-based cohorts. Treatments included thiazide diuretics (TDs), angiotensin converting enzyme inhibitors (ACE-Is), and dihydropyridine calcium channel blockers (dCCBs) and were compared in a pairwise manner. We performed fixed effects inverse variance weighted meta-analyses of main effects of drugs and 2.5 million SNP-by-drug interaction estimates. RESULTS: We observed that dCCBs versus TDs were associated with higher LVM after adjusting for covariates (p = 0.001). We report three SNPs at a single locus on chromosome 20 that modified the association between RWT and treatment when comparing dCCBs to ACE-Is with consistent effects across cohorts (smallest p = 4.7 × 10 , minor allele frequency range 0.09-0.12). This locus has been linked to LV hypertrophy in a previous study. A marginally significant locus in BICD1 (rs326641) was validated in an external population. CONCLUSIONS: Our study identified one locus having genome-wide significant SNP-by-drug interaction effect on RWT among dCCB users in comparison to ACE-I users. Upon additional validation in future studies, our findings can enhance the precision of medical approaches in hypertension treatment.
Keywords: African Americans; Angiotensin-Converting Enzyme Inhibitors; Antihypertensive Agents; Calcium Channel Blockers; Humans; Observational Studies as Topic; Pharmacogenomic Variants; Polymorphism, Single Nucleotide; Sodium Chloride Symporter Inhibitors; Ventricular Dysfunction, Left

Genome-wide meta-analysis of variant-by-diuretic interactions as modulators of lipid traits in persons of European and African ancestry. - de Las Fuentes, L; Sung, Y J; Sitlani, C M; Avery, C L; Bartz, T M; Keyser, C de; Evans, D S; Li, X; Musani, S K; Ruiter, R; Smith, A V; Sun, F; et al. (Pharmacogenomics J, 2019)
Hypertension (HTN) is a significant risk factor for cardiovascular morbidity and mortality. Metabolic abnormalities, including adverse cholesterol and triglycerides (TG) profiles, are frequent comorbid findings with HTN and contribute to cardiovascular disease. Diuretics, which are used to treat HTN and heart failure, have been associated with worsening of fasting lipid concentrations. Genome-wide meta-analyses with 39,710 European-ancestry (EA) individuals and 9925 African-ancestry (AA) individuals were performed to identify genetic variants that modify the effect of loop or thiazide diuretic use on blood lipid concentrations. Both longitudinal and cross sectional data were used to compute cohort-specific interaction results, which were then combined through meta-analysis in each ancestry. These ancestry-specific results were further combined through trans-ancestry meta-analysis. Analysis of EA data identified two genome-wide significant (p < 5 × 10) loci with single nucleotide variant (SNV)-loop diuretic interaction on TG concentrations (including COL11A1). Analysis of AA data identified one genome-wide significant locus adjacent to BMP2 with SNV-loop diuretic interaction on TG concentrations. Trans-ancestry analysis strengthened evidence of association for SNV-loop diuretic interaction at two loci (KIAA1217 and BAALC). There were few significant SNV-thiazide diuretic interaction associations on TG concentrations and for either diuretic on cholesterol concentrations. Several promising loci were identified that may implicate biologic pathways that contribute to adverse metabolic side effects from diuretic therapy.

Genomic and transcriptomic association studies identify 16 novel susceptibility loci for venous thromboembolism. - Lindström, Sara; Wang, Lu; Smith, Erin N; Gordon, William; van Hylckama Vlieg, Astrid; de Andrade, Mariza; Brody, Jennifer A; Pattee, Jack W; Haessler, Jeffrey; Brumpton, Ben M; Chasman, Daniel I; Suchon, Pierre; et al. (Blood, 2019)
Venous thromboembolism (VTE) is a significant contributor to morbidity and mortality. To advance our understanding of the biology contributing to VTE, we conducted a genome-wide association study (GWAS) of VTE and a transcriptome-wide association study (TWAS) based on imputed gene expression from whole blood and liver. We meta-analyzed GWAS data from 18 studies for 30 234 VTE cases and 172 122 controls and assessed the association between 12 923 718 genetic variants and VTE. We generated variant prediction scores of gene expression from whole blood and liver tissue and assessed them for association with VTE. Mendelian randomization analyses were conducted for traits genetically associated with novel VTE loci. We identified 34 independent genetic signals for VTE risk from GWAS meta-analysis, of which 14 are newly reported associations. This included 11 newly associated genetic loci (C1orf198, PLEK, OSMR-AS1, NUGGC/SCARA5, GRK5, MPHOSPH9, ARID4A, PLCG2, SMG6, EIF5A, and STX10) of which 6 replicated, and 3 new independent signals in 3 known genes. Further, TWAS identified 5 additional genetic loci with imputed gene expression levels differing between cases and controls in whole blood (SH2B3, SPSB1, RP11-747H7.3, RP4-737E23.2) and in liver (ERAP1). At some GWAS loci, we found suggestive evidence that the VTE association signal for novel and previously known regions colocalized with expression quantitative trait locus signals. Mendelian randomization analyses suggested that blood traits may contribute to the underlying risk of VTE. To conclude, we identified 16 novel susceptibility loci for VTE; for some loci, the association signals are likely mediated through gene expression of nearby genes.

Genomics of 1 million parent lifespans implicates novel pathways and common diseases and distinguishes survival chances. - Timmers, Paul Rhj; Mounier, Ninon; Läll, Kristi; Fischer, Krista; Ning, Zheng; Feng, Xiao; Bretherick, Andrew D; Clark, David W; Agbessi, M; Ahsan, H; Alves, I; Andiappan, A; et al. (Elife, 2019)
We use a genome-wide association of 1 million parental lifespans of genotyped subjects and data on mortality risk factors to validate previously unreplicated findings near , , , , , and 13q21.31, and identify and replicate novel findings near , , and . We also validate previous findings near 5q33.3/ and , whilst finding contradictory evidence at other loci. Gene set and cell-specific analyses show that expression in foetal brain cells and adult dorsolateral prefrontal cortex is enriched for lifespan variation, as are gene pathways involving lipid proteins and homeostasis, vesicle-mediated transport, and synaptic function. Individual genetic variants that increase dementia, cardiovascular disease, and lung cancer - but not other cancers - explain the most variance. Resulting polygenic scores show a mean lifespan difference of around five years of life across the deciles. Editorial note: This article has been through an editorial process in which the authors decide how to respond to the issues raised during peer review. The Reviewing Editor's assessment is that all the issues have been addressed (see decision letter).

{The impact of APOE genotype on survival: Results of 38,537 participants from six population-based cohorts (E2-CHARGE) - Wolters, F. J.; Yang, Q.; Biggs, M. L.; Jakobsdottir, J.; Li, S.; Evans, D. S.; Bis, J. C.; Harris, T. B.; Vasan, R. S.; Zilhao, N. R.; Ghanbari, M.; Ikram, M. A.; et al. (PLoS One, 2019)
Apolipoprotein E is a glycoprotein best known as a mediator and regulator of lipid transport and uptake. The APOE-Îµ4 allele has long been associated with increased risks of Alzheimer's disease and mortality, but the effect of the less prevalent APOE-Îµ2 allele on diseases in the elderly and survival remains elusive.\ We aggregated data of 38,537 individuals of European ancestry (mean age 65.5 years; 55.6% women) from six population-based cohort studies (Rotterdam Study, AGES-Reykjavik Study, Cardiovascular Health Study, Health-ABC Study, and the family-based Framingham Heart Study and Long Life Family Study) to determine the association of APOE, and in particular APOE-Îµ2, with survival in the population.\ During a mean follow-up of 11.7 years, 17,021 individuals died. Compared with homozygous APOE-Îµ3 carriers, APOE-Îµ2 carriers were at lower risk of death (hazard ratio,95% confidence interval: 0.94,0.90-0.99; P = 1.1*10-2), whereas APOE-Îµ4 carriers were at increased risk of death (HR 1.17,1.12-1.21; P = 2.8*10-16). APOE was associated with mortality risk in a dose-dependent manner, with risk estimates lowest for homozygous APOE-Îµ2 (HR 0.89,0.74-1.08), and highest for homozygous APOE-Îµ4 (HR 1.52,1.37-1.70). After censoring for dementia, effect estimates remained similar for APOE-Îµ2 (HR 0.95,0.90-1.01), but attenuated for APOE-Îµ4 (HR 1.07,1.01-1.12). Results were broadly similar across cohorts, and did not differ by age or sex. APOE genotype was associated with baseline lipid fractions (e.g. mean difference(95%CI) in LDL(mg/dL) for Îµ2 versus Îµ33: -17.1(-18.1-16.0), and Îµ4 versus Îµ33: +5.7(4.8;6.5)), but the association between APOE and mortality was unaltered after adjustment for baseline LDL or cardiovascular disease. Given the European ancestry of the study population, results may not apply to other ethnicities.\ Compared with APOE-Îµ3, APOE-Îµ2 is associated with prolonged survival, whereas mortality risk is increased for APOE-Îµ4 carriers. Further collaborative efforts are needed to unravel the role of APOE and in particular APOE-Îµ2 in health and disease.

Impact of Rare and Common Genetic Variants on Diabetes Diagnosis by Hemoglobin A1c in Multi-Ancestry Cohorts: The Trans-Omics for Precision Medicine Program. - Sarnowski, Chloe; Leong, Aaron; Raffield, Laura M; Wu, Peitao; de Vries, Paul S; DiCorpo, Daniel; Guo, Xiuqing; Xu, Huichun; Liu, Yongmei; Zheng, Xiuwen; Hu, Yao; Brody, Jennifer A; et al. (Am J Hum Genet, 2019)
Hemoglobin A1c (HbA1c) is widely used to diagnose diabetes and assess glycemic control in individuals with diabetes. However, nonglycemic determinants, including genetic variation, may influence how accurately HbA1c reflects underlying glycemia. Analyzing the NHLBI Trans-Omics for Precision Medicine (TOPMed) sequence data in 10,338 individuals from five studies and four ancestries (6,158 Europeans, 3,123 African-Americans, 650 Hispanics, and 407 East Asians), we confirmed five regions associated with HbA1c (GCK in Europeans and African-Americans, HK1 in Europeans and Hispanics, FN3K and/or FN3KRP in Europeans, and G6PD in African-Americans and Hispanics) and we identified an African-ancestry-specific low-frequency variant (rs1039215 in HBG2 and HBE1, minor allele frequency (MAF) = 0.03). The most associated G6PD variant (rs1050828-T, p.Val98Met, MAF = 12% in African-Americans, MAF = 2% in Hispanics) lowered HbA1c (-0.88% in hemizygous males, -0.34% in heterozygous females) and explained 23% of HbA1c variance in African-Americans and 4% in Hispanics. Additionally, we identified a rare distinct G6PD coding variant (rs76723693, p.Leu353Pro, MAF = 0.5%; -0.98% in hemizygous males, -0.46% in heterozygous females) and detected significant association with HbA1c when aggregating rare missense variants in G6PD. We observed similar magnitude and direction of effects for rs1039215 (HBG2) and rs76723693 (G6PD) in the two largest TOPMed African American cohorts, and we replicated the rs76723693 association in the UK Biobank African-ancestry participants. These variants in G6PD and HBG2 were monomorphic in the European and Asian samples. African or Hispanic ancestry individuals carrying G6PD variants may be underdiagnosed for diabetes when screened with HbA1c. Thus, assessment of these variants should be considered for incorporation into precision medicine approaches for diabetes diagnosis.

A large-scale exome array analysis of venous thromboembolism. - Lindström, Sara; Brody, Jennifer A; Turman, Constance; Germain, Marine; Bartz, Traci M; Smith, Erin N; Chen, Ming-Huei; Puurunen, Marja; Chasman, Daniel; Hassler, Jeffrey; Pankratz, Nathan; Basu, Saonli; et al. (Genet Epidemiol, 2019)
Although recent Genome-Wide Association Studies have identified novel associations for common variants, there has been no comprehensive exome-wide search for low-frequency variants that affect the risk of venous thromboembolism (VTE). We conducted a meta-analysis of 11 studies comprising 8,332 cases and 16,087 controls of European ancestry and 382 cases and 1,476 controls of African American ancestry genotyped with the Illumina HumanExome BeadChip. We used the seqMeta package in R to conduct single variant and gene-based rare variant tests. In the single variant analysis, we limited our analysis to the 64,794 variants with at least 40 minor alleles across studies (minor allele frequency [MAF] ~0.08%). We confirmed associations with previously identified VTE loci, including ABO, F5, F11, and FGA. After adjusting for multiple testing, we observed no novel significant findings in single variant or gene-based analysis. Given our sample size, we had greater than 80% power to detect minimum odds ratios greater than 1.5 and 1.8 for a single variant with MAF of 0.01 and 0.005, respectively. Larger studies and sequence data may be needed to identify novel low-frequency and rare variants associated with VTE risk.

{Low thyroid function is not associated with an accelerated deterioration in renal function - Meuwese, C. L.; van Diepen, M.; Cappola, A. R.; Sarnak, M. J.; Shlipak, M. G.; Bauer, D. C.; Fried, L. P.; Iacoviello, M.; Vaes, B.; Degryse, J.; Khaw, K. T.; Luben, R. N.; et al. (Nephrol Dial Transplant, 2019)
Chronic kidney disease (CKD) is frequently accompanied by thyroid hormone dysfunction. It is currently unclear whether these alterations are the cause or consequence of CKD. This study aimed at studying the effect of thyroid hormone alterations on renal function in cross-sectional and longitudinal analyses in individuals from all adult age groups.\ Individual participant data (IPD) from 16 independent cohorts having measured thyroid stimulating hormone, free thyroxine levels and creatinine levels were included. Thyroid hormone status was defined using clinical cut-off values. Estimated glomerular filtration rates (eGFR) were calculated by means of the four-variable Modification of Diet in Renal Disease (MDRD) formula. For this IPD meta-analysis, eGFR at baseline and eGFR change during follow-up were computed by fitting linear regression models and linear mixed models in each cohort separately. Effect estimates were pooled using random effects models.\ A total of 72 856 individuals from 16 different cohorts were included. At baseline, individuals with overt hypothyroidism (n = 704) and subclinical hypothyroidism (n = 3356) had a average (95% confidence interval) -4.07 (-6.37 to -1.78) and -2.40 (-3.78 to -1.02) mL/min/1.73 m2 lower eGFR as compared with euthyroid subjects (n = 66 542). In (subclinical) hyperthyroid subjects (n = 2254), average eGFR was 3.01 (1.50-4.52) mL/min/1.73 m2 higher. During 329 713 patient years of follow-up, eGFR did not decline more rapidly in individuals with low thyroid function compared with individuals with normal thyroid function.\ Low thyroid function is not associated with a deterioration of renal function. The cross-sectional association may be explained by renal dysfunction causing thyroid hormone alterations.

Mendelian randomization evaluation of causal effects of fibrinogen on incident coronary heart disease. - Ward-Caviness, Cavin K; de Vries, Paul S; Wiggins, Kerri L; Huffman, Jennifer E; Yanek, Lisa R; Bielak, Lawrence F; Giulianini, Franco; Guo, Xiuqing; Kleber, Marcus E; Kacprowski, Tim; Groß, Stefan; Petersman, Astrid; et al. (PLoS One, 2019)
BACKGROUND: Fibrinogen is an essential hemostatic factor and cardiovascular disease risk factor. Early attempts at evaluating the causal effect of fibrinogen on coronary heart disease (CHD) and myocardial infraction (MI) using Mendelian randomization (MR) used single variant approaches, and did not take advantage of recent genome-wide association studies (GWAS) or multi-variant, pleiotropy robust MR methodologies. METHODS AND FINDINGS: We evaluated evidence for a causal effect of fibrinogen on both CHD and MI using MR. We used both an allele score approach and pleiotropy robust MR models. The allele score was composed of 38 fibrinogen-associated variants from recent GWAS. Initial analyses using the allele score used a meta-analysis of 11 European-ancestry prospective cohorts, free of CHD and MI at baseline, to examine incidence CHD and MI. We also applied 2 sample MR methods with data from a prevalent CHD and MI GWAS. Results are given in terms of the hazard ratio (HR) or odds ratio (OR), depending on the study design, and associated 95% confidence interval (CI). In single variant analyses no causal effect of fibrinogen on CHD or MI was observed. In multi-variant analyses using incidence CHD cases and the allele score approach, the estimated causal effect (HR) of a 1 g/L higher fibrinogen concentration was 1.62 (CI = 1.12, 2.36) when using incident cases and the allele score approach. In 2 sample MR analyses that accounted for pleiotropy, the causal estimate (OR) was reduced to 1.18 (CI = 0.98, 1.42) and 1.09 (CI = 0.89, 1.33) in the 2 most precise (smallest CI) models, out of 4 models evaluated. In the 2 sample MR analyses for MI, there was only very weak evidence of a causal effect in only 1 out of 4 models. CONCLUSIONS: A small causal effect of fibrinogen on CHD is observed using multi-variant MR approaches which account for pleiotropy, but not single variant MR approaches. Taken together, results indicate that even with large sample sizes and multi-variant approaches MR analyses still cannot exclude the null when estimating the causal effect of fibrinogen on CHD, but that any potential causal effect is likely to be much smaller than observed in epidemiological studies.

{A meta-analysis of genome-wide association studies identifies multiple longevity genes - Deelen, J.; Evans, D. S.; Arking, D. E.; Tesi, N.; Nygaard, M.; Liu, X.; Wojczynski, M. K.; Biggs, M. L.; van der Spek, A.; Atzmon, G.; Ware, E. B.; Sarnowski, C.; et al. (Nat Commun, 2019)
Human longevity is heritable, but genome-wide association (GWA) studies have had limited success. Here, we perform two meta-analyses of GWA studies of a rigorous longevity phenotype definition including 11,262/3484 cases surviving at or beyond the age corresponding to the 90th/99th survival percentile, respectively, and 25,483 controls whose age at death or at last contact was at or below the age corresponding to the 60th survival percentile. Consistent with previous reports, rs429358 (apolipoprotein E (ApoE) Îµ4) is associated with lower odds of surviving to the 90th and 99th percentile age, while rs7412 (ApoE Îµ2) shows the opposite. Moreover, rs7676745, located near GPR78, associates with lower odds of surviving to the 90th percentile age. Gene-level association analysis reveals a role for tissue-specific expression of multiple genes in longevity. Finally, genetic correlation of the longevity GWA results with that of several disease-related phenotypes points to a shared genetic architecture between health and longevity.

{A meta-analysis of genome-wide association studies identifies multiple longevity genes - Deelen, J.; Evans, D. S.; Arking, D. E.; Tesi, N.; Nygaard, M.; Liu, X.; Wojczynski, M. K.; Biggs, M. L.; van der Spek, A.; Atzmon, G.; Ware, E. B.; Sarnowski, C.; et al. (Nat Commun, 2019)
2) shows the opposite. Moreover, rs7676745, located near GPR78, associates with lower odds of surviving to the 90th percentile age. Gene-level association analysis reveals a role for tissue-specific expression of multiple genes in longevity. Finally, genetic correlation of the longevity GWA results with that of several disease-related phenotypes points to a shared genetic architecture between health and longevity.

{Meta-Analysis of Genomewide Association Studies Reveals Genetic Variants for Hip Bone Geometry - Hsu, Y. H.; Estrada, K.; Evangelou, E.; Ackert-Bicknell, C.; Akesson, K.; Beck, T.; Brown, S. J.; Capellini, T.; Carbone, L.; Cauley, J.; Cheung, C. L.; Cummings, S. R.; et al. (J Bone Miner Res, 2019)
Hip geometry is an important predictor of fracture. We performed a meta-analysis of GWAS studies in adults to identify genetic variants that are associated with proximal femur geometry phenotypes. We analyzed four phenotypes: (i) femoral neck length; (ii) neck-shaft angle; (iii) femoral neck width, and (iv) femoral neck section modulus, estimated from DXA scans using algorithms of hip structure analysis. In the Discovery stage, 10 cohort studies were included in the fixed-effect meta-analysis, with up to 18,719 men and women ages 16 to 93 years. Association analyses were performed with ∼2.5 million polymorphisms under an additive model adjusted for age, body mass index, and height. Replication analyses of meta-GWAS significant loci (at adjusted genomewide significance [GWS], threshold p ≤ 2.6 × 10-8 ) were performed in seven additional cohorts in silico. We looked up SNPs associated in our analysis, for association with height, bone mineral density (BMD), and fracture. In meta-analysis (combined Discovery and Replication stages), GWS associations were found at 5p15 (IRX1 and ADAMTS16); 5q35 near FGFR4; at 12p11 (in CCDC91); 11q13 (near LRP5 and PPP6R3 (rs7102273)). Several hip geometry signals overlapped with BMD, including LRP5 (chr. 11). Chr. 11 SNP rs7102273 was associated with any-type fracture (p = 7.5 × 10-5 ). We used bone transcriptome data and discovered several significant eQTLs, including rs7102273 and PPP6R3 expression (p = 0.0007), and rs6556301 (intergenic, chr.5 near FGFR4) and PDLIM7 expression (p = 0.005). In conclusion, we found associations between several genes and hip geometry measures that explained 12% to 22% of heritability at different sites. The results provide a defined set of genes related to biological pathways relevant to BMD and etiology of bone fragility. © 2019 American Society for Bone and Mineral Research.

Multi-Ancestry Genome-Wide Association Study of Lipid Levels Incorporating Gene-Alcohol Interactions. - de Vries, Paul S; Brown, Michael R; Bentley, Amy R; Sung, Yun J; Winkler, Thomas W; Ntalla, Ioanna; Schwander, Karen; Kraja, Aldi T; Guo, Xiuqing; Franceschini, Nora; Cheng, Ching-Yu; Sim, Xueling; et al. (Am J Epidemiol, 2019)
An individual's lipid profile is influenced by genetic variants and alcohol consumption, but the contribution of interactions between these exposures has not been studied. We therefore incorporated gene-alcohol interactions into a multi-ancestry genome-wide association study of levels of high-density lipoprotein cholesterol, low-density lipoprotein cholesterol, and triglycerides. We included 45 studies in Stage 1 (genome-wide discovery) and 66 studies in Stage 2 (focused follow-up), for a total of 394,584 individuals from five ancestry groups. Genetic main and interaction effects were jointly assessed by a 2 degrees of freedom (DF) test, and a 1 DF test was used to assess the interaction effects alone. Variants at 495 loci were at least suggestively associated (P < 1 × 10-6) with lipid levels in Stage 1 and were evaluated in Stage 2, followed by combined analyses of Stage 1 and Stage 2. In the combined analysis of Stage 1 and Stage 2, 147 independent loci were associated with lipid levels at P < 5 × 10-8 using 2 DF tests, of which 18 were novel. No genome-wide significant associations were found testing the interaction effect alone. The novel loci included several genes (PCSK5, VEGFB, and A1CF) with a putative role in lipid metabolism based on existing evidence from cellular and experimental models.

Multi-ancestry genome-wide gene-smoking interaction study of 387,272 individuals identifies new loci associated with serum lipids. - Bentley, Amy R; Sung, Yun J; Brown, Michael R; Winkler, Thomas W; Kraja, Aldi T; Ntalla, Ioanna; Schwander, Karen; Chasman, Daniel I; Lim, Elise; Deng, Xuan; Guo, Xiuqing; Liu, Jingmin; et al. (Nat Genet, 2019)
The concentrations of high- and low-density-lipoprotein cholesterol and triglycerides are influenced by smoking, but it is unknown whether genetic associations with lipids may be modified by smoking. We conducted a multi-ancestry genome-wide gene-smoking interaction study in 133,805 individuals with follow-up in an additional 253,467 individuals. Combined meta-analyses identified 13 new loci associated with lipids, some of which were detected only because association differed by smoking status. Additionally, we demonstrate the importance of including diverse populations, particularly in studies of interactions with lifestyle factors, where genomic and lifestyle differences by ancestry may contribute to novel findings.

{A multi-ancestry genome-wide study incorporating gene-smoking interactions identifies multiple new loci for pulse pressure and mean arterial pressure - Sung, Y. J.; de Las Fuentes, L.; Winkler, T. W.; Chasman, D. I.; Bentley, A. R.; Kraja, A. T.; Ntalla, I.; Warren, H. R.; Guo, X.; Schwander, K.; Manning, A. K.; Brown, M. R.; et al. (Hum. Mol. Genet., 2019)
Elevated blood pressure (BP), a leading cause of global morbidity and mortality, is influenced by both genetic and lifestyle factors. Cigarette smoking is one such lifestyle factor. Across five ancestries, we performed a genome-wide gene-smoking interaction study of mean arterial pressure (MAP) and pulse pressure (PP) in 129 913 individuals in stage 1 and follow-up analysis in 480 178 additional individuals in stage 2. We report here 136 loci significantly associated with MAP and/or PP. Of these, 61 were previously published through main-effect analysis of BP traits, 37 were recently reported by us for systolic BP and/or diastolic BP through gene-smoking interaction analysis and 38 were newly identified (P < 5 Ã— 10-8, false discovery rate < 0.05). We also identified nine new signals near known loci. Of the 136 loci, 8 showed significant interaction with smoking status. They include CSMD1 previously reported for insulin resistance and BP in the spontaneously hypertensive rats. Many of the 38 new loci show biologic plausibility for a role in BP regulation. SLC26A7 encodes a chloride/bicarbonate exchanger expressed in the renal outer medullary collecting duct. AVPR1A is widely expressed, including in vascular smooth muscle cells, kidney, myocardium and brain. FHAD1 is a long non-coding RNA overexpressed in heart failure. TMEM51 was associated with contractile function in cardiomyocytes. CASP9 plays a central role in cardiomyocyte apoptosis. Identified only in African ancestry were 30 novel loci. Our findings highlight the value of multi-ancestry investigations, particularly in studies of interaction with lifestyle factors, where genomic and lifestyle differences may contribute to novel findings.

Multi-ancestry sleep-by-SNP interaction analysis in 126,926 individuals reveals lipid loci stratified by sleep duration. - Noordam, Raymond; Bos, Maxime M; Wang, Heming; Winkler, Thomas W; Bentley, Amy R; Kilpeläinen, Tuomas O; de Vries, Paul S; Sung, Yun Ju; Schwander, Karen; Cade, Brian E; Manning, Alisa; Aschard, Hugues; et al. (Nat Commun, 2019)
Both short and long sleep are associated with an adverse lipid profile, likely through different biological pathways. To elucidate the biology of sleep-associated adverse lipid profile, we conduct multi-ancestry genome-wide sleep-SNP interaction analyses on three lipid traits (HDL-c, LDL-c and triglycerides). In the total study sample (discovery + replication) of 126,926 individuals from 5 different ancestry groups, when considering either long or short total sleep time interactions in joint analyses, we identify 49 previously unreported lipid loci, and 10 additional previously unreported lipid loci in a restricted sample of European-ancestry cohorts. In addition, we identify new gene-sleep interactions for known lipid loci such as LPL and PCSK9. The previously unreported lipid loci have a modest explained variance in lipid levels: most notable, gene-short-sleep interactions explain 4.25% of the variance in triglyceride level. Collectively, these findings contribute to our understanding of the biological mechanisms involved in sleep-associated adverse lipid profiles.

Multi-ancestry study of blood lipid levels identifies four loci interacting with physical activity. - Kilpeläinen, Tuomas O; Bentley, Amy R; Noordam, Raymond; Sung, Yun Ju; Schwander, Karen; Winkler, Thomas W; Jakupović, Hermina; Chasman, Daniel I; Manning, Alisa; Ntalla, Ioanna; Aschard, Hugues; Brown, Michael R; et al. (Nat Commun, 2019)
Many genetic loci affect circulating lipid levels, but it remains unknown whether lifestyle factors, such as physical activity, modify these genetic effects. To identify lipid loci interacting with physical activity, we performed genome-wide analyses of circulating HDL cholesterol, LDL cholesterol, and triglyceride levels in up to 120,979 individuals of European, African, Asian, Hispanic, and Brazilian ancestry, with follow-up of suggestive associations in an additional 131,012 individuals. We find four loci, in/near CLASP1, LHX1, SNTA1, and CNTNAP2, that are associated with circulating lipid levels through interaction with physical activity; higher levels of physical activity enhance the HDL cholesterol-increasing effects of the CLASP1, LHX1, and SNTA1 loci and attenuate the LDL cholesterol-increasing effect of the CNTNAP2 locus. The CLASP1, LHX1, and SNTA1 regions harbor genes linked to muscle function and lipid metabolism. Our results elucidate the role of physical activity interactions in the genetic contribution to blood lipid levels.
Keywords: Adolescent; Adult; African Continental Ancestry Group; Aged; Aged, 80 and over; Asian Continental Ancestry Group; Brazil; Calcium-Binding Proteins; Cholesterol; Cholesterol, HDL; Cholesterol, LDL; European Continental Ancestry Group; Exercise; Female; Genetic Loci; Genome-Wide Association Study; Genotype; Hispanic Americans; Humans; LIM-Homeodomain Proteins; Lipid Metabolism; Lipids; Male; Membrane Proteins; Microtubule-Associated Proteins; Middle Aged; Muscle Proteins; Nerve Tissue Proteins; Transcription Factors; Triglycerides; Young Adult

Multiethnic Genome-Wide Association Study of Diabetic Retinopathy Using Liability Threshold Modeling of Duration of Diabetes and Glycemic Control. - Pollack, Samuela; Igo, Robert P; Jensen, Richard A; Christiansen, Mark; Li, Xiaohui; Cheng, Ching-Yu; Ng, Maggie C Y; Smith, Albert V; Rossin, Elizabeth J; Segrè, Ayellet V; Davoudi, Samaneh; Tan, Gavin S; et al. (Diabetes, 2019)
To identify genetic variants associated with diabetic retinopathy (DR), we performed a large multiethnic genome-wide association study. Discovery included eight European cohorts ( = 3,246) and seven African American cohorts ( = 2,611). We meta-analyzed across cohorts using inverse-variance weighting, with and without liability threshold modeling of glycemic control and duration of diabetes. Variants with a value <1 × 10 were investigated in replication cohorts that included 18,545 European, 16,453 Asian, and 2,710 Hispanic subjects. After correction for multiple testing, the C allele of rs142293996 in an intron of nuclear VCP-like () was associated with DR in European discovery cohorts ( = 2.1 × 10), but did not reach genome-wide significance after meta-analysis with replication cohorts. We applied the Disease Association Protein-Protein Link Evaluator (DAPPLE) to our discovery results to test for evidence of risk being spread across underlying molecular pathways. One protein-protein interaction network built from genes in regions associated with proliferative DR was found to have significant connectivity ( = 0.0009) and corroborated with gene set enrichment analyses. These findings suggest that genetic variation in as well as variation within a protein-protein interaction network that includes genes implicated in inflammation, may influence risk for DR.

{New alcohol-related genes suggest shared genetic mechanisms with neuropsychiatric disorders - Evangelou, E.; Gao, H.; Chu, C.; Ntritsos, G.; Blakeley, P.; Butts, A. R.; Pazoki, R.; Suzuki, H.; Koskeridis, F.; Yiorkas, A. M.; Karaman, I.; Elliott, J.; et al. (Nat Hum Behav, 2019)
Excessive alcohol consumption is one of the main causes of death and disability worldwide. Alcohol consumption is a heritable complex trait. Here we conducted a meta-analysis of genome-wide association studies of alcohol consumption (g d-1) from the UK Biobank, the Alcohol Genome-Wide Consortium and the Cohorts for Heart and Aging Research in Genomic Epidemiology Plus consortia, collecting data from 480,842 people of European descent to decipher the genetic architecture of alcohol intake. We identified 46 new common loci and investigated their potential functional importance using magnetic resonance imaging data and gene expression studies. We identify genetic pathways associated with alcohol consumption and suggest genetic mechanisms that are shared with neuropsychiatric disorders such as schizophrenia.

No causal effects of serum urate levels on the risk of chronic kidney disease: A Mendelian randomization study. - Jordan, Daniel M; Choi, Hyon K; Verbanck, Marie; Topless, Ruth; Won, Hong-Hee; Nadkarni, Girish; Merriman, Tony R; Do, Ron (PLoS Med, 2019)
BACKGROUND: Studies have shown strong positive associations between serum urate (SU) levels and chronic kidney disease (CKD) risk; however, whether the relation is causal remains uncertain. We evaluate whether genetic data are consistent with a causal impact of SU level on the risk of CKD and estimated glomerular filtration rate (eGFR). METHODS AND FINDINGS: We used Mendelian randomization (MR) methods to evaluate the presence of a causal effect. We used aggregated genome-wide association data (N = 110,347 for SU, N = 69,374 for gout, N = 133,413 for eGFR, N = 117,165 for CKD), electronic-medical-record-linked UK Biobank data (N = 335,212), and population-based cohorts (N = 13,425), all in individuals of European ancestry, for SU levels and CKD. Our MR analysis showed that SU has a causal effect on neither eGFR level nor CKD risk across all MR analyses (all P > 0.05). These null associations contrasted with our epidemiological association findings from the 4 population-based cohorts (change in eGFR level per 1-mg/dl [59.48 μmol/l] increase in SU: -1.99 ml/min/1.73 m2; 95% CI -2.86 to -1.11; P = 8.08 × 10(-6); odds ratio [OR] for CKD: 1.48; 95% CI 1.32 to 1.65; P = 1.52 × 10(-11)). In contrast, the same MR approaches showed that SU has a causal effect on the risk of gout (OR estimates ranging from 3.41 to 6.04 per 1-mg/dl increase in SU, all P < 10-3), which served as a positive control of our approach. Overall, our MR analysis had >99% power to detect a causal effect of SU level on the risk of CKD of the same magnitude as the observed epidemiological association between SU and CKD. Limitations of this study include the lifelong effect of a genetic perturbation not being the same as an acute perturbation, the inability to study non-European populations, and some sample overlap between the datasets used in the study. CONCLUSIONS: Evidence from our series of causal inference approaches using genetics does not support a causal effect of SU level on eGFR level or CKD risk. Reducing SU levels is unlikely to reduce the risk of CKD development.
Keywords: Adult; Age Factors; Female; Genome-Wide Association Study; Glomerular Filtration Rate; Humans; Male; Mendelian Randomization Analysis; Renal Insufficiency, Chronic; Sex Factors; Uric Acid; Young Adult

NT -pro BNP as a Mediator of the Racial Difference in Incident Atrial Fibrillation and Heart Failure. - Whitman, Isaac R; Vittinghoff, Eric; deFilippi, Christopher R; Gottdiener, John S; Alonso, Alvaro; Psaty, Bruce M; Heckbert, Susan R; Hoogeveen, Ron C; Arking, Dan E; Selvin, Elizabeth; Chen, Lin Y; Dewland, Thomas A; et al. (J Am Heart Assoc, 2019)
Background Blacks harbor more cardiovascular risk factors than whites, but experience less atrial fibrillation ( AF ). Conversely, whites may have a lower risk of heart failure ( CHF ). N-terminal pro-B-type natriuretic peptide ( NT -pro BNP) levels are higher in whites, predict incident AF , and have diuretic effects in the setting of increased ventricular diastolic pressures, potentially providing a unifying explanation for these racial differences. Methods and Results We used data from the CHS (Cardiovascular Health Study) to determine the degree to which baseline NT -pro BNP levels mediate the relationships between race and incident AF and CHF by comparing beta estimates between models with and without NT -pro BNP . The ARIC (Atherosclerosis Risk in Communities) study was used to assess reproducibility. Among 4731 CHS (770 black) and 12 418 ARIC (3091 black) participants, there were 1277 and 1253 incident AF events, respectively. Whites had higher baseline NT -pro BNP ( CHS : 40% higher than blacks; 95% CI , 29-53; ARIC : 39% higher; 95% CI , 33-46) and had a greater risk of incident AF compared with blacks ( CHS : adjusted hazard ratio, 1.60; 95% CI , 1.31-1.93; ARIC : hazard ratio, 1.93; 95% CI , 1.57-2.27). NT -pro BNP levels explained a significant proportion of the racial difference in AF risk ( CHS : 36.2%; 95% CI , 23.2-69.2%; ARIC : 24.6%; 95% CI , 14.8-39.6%). Contrary to our hypothesis, given an increased risk of CHF among whites in CHS (adjusted hazard ratio, 1.20; 95% CI , 1.05-1.47) and the absence of a significant association between race and CHF in ARIC (adjusted hazard ratio, 1.07; 95% CI , 0.94-1.23), CHF -related mediation analyses were not performed. Conclusions A substantial portion of the relationship between race and AF was statistically explained by baseline NT -pro BNP levels. No consistent relationship between race and CHF was observed.

{Omega-3 Fatty Acids and Genome-Wide Interaction Analyses Reveal DPP10-Pulmonary Function Association - Xu, J.; Gaddis, N. C.; Bartz, T. M.; Hou, R.; Manichaikul, A. W.; Pankratz, N.; Smith, A. V.; Sun, F.; Terzikhan, N.; Markunas, C. A.; Patchen, B. K.; Schu, M.; et al. (Am J Respir Crit Care Med, 2019)
Omega-3 polyunsaturated fatty acids (n-3 PUFAs) have anti-inflammatory properties that could benefit adults with comprised pulmonary health.\ To investigate n-3 PUFA associations with spirometric measures of pulmonary function tests (PFTs) and determine underlying genetic susceptibility.\ Associations of n-3 PUFA biomarkers (α-linolenic acid, eicosapentaenoic acid, docosapentaenoic acid [DPA], and docosahexaenoic acid [DHA]) were evaluated with PFTs (FEV1, FVC, and FEV1/FVC) in meta-analyses across seven cohorts from the Cohorts for Heart and Aging Research in Genomic Epidemiology Consortium (N = 16,134 of European or African ancestry). PFT-associated n-3 PUFAs were carried forward to genome-wide interaction analyses in the four largest cohorts (N = 11,962) and replicated in one cohort (N = 1,687). Cohort-specific results were combined using joint 2 degree-of-freedom (2df) meta-analyses of SNP associations and their interactions with n-3 PUFAs.\ DPA and DHA were positively associated with FEV1 and FVC (P < 0.025), with evidence for effect modification by smoking and by sex. Genome-wide analyses identified a novel association of rs11693320-an intronic DPP10 SNP-with FVC when incorporating an interaction with DHA, and the finding was replicated (P2df = 9.4 × 10-9 across discovery and replication cohorts). The rs11693320-A allele (frequency, ∼80%) was associated with lower FVC (PSNP = 2.1 × 10-9; βSNP = -161.0 ml), and the association was attenuated by higher DHA levels (PSNP×DHA interaction = 2.1 × 10-7; βSNP×DHA interaction = 36.2 ml).\ We corroborated beneficial effects of n-3 PUFAs on pulmonary function. By modeling genome-wide n-3 PUFA interactions, we identified a novel DPP10 SNP association with FVC that was not detectable in much larger studies ignoring this interaction.

Pharmacogenomics of statin-related myopathy: Meta-analysis of rare variants from whole-exome sequencing. - Floyd, James S; Bloch, Katarzyna M; Brody, Jennifer A; Maroteau, Cyrielle; Siddiqui, Moneeza K; Gregory, Richard; Carr, Daniel F; Molokhia, Mariam; Liu, Xiaoming; Bis, Joshua C; Ahmed, Ammar; Liu, Xuan; et al. (PLoS One, 2019)
AIMS: Statin-related myopathy (SRM), which includes rhabdomyolysis, is an uncommon but important adverse drug reaction because the number of people prescribed statins world-wide is large. Previous association studies of common genetic variants have had limited success in identifying a genetic basis for this adverse drug reaction. We conducted a multi-site whole-exome sequencing study to investigate whether rare coding variants confer an increased risk of SRM. METHODS AND RESULTS: SRM 3-5 cases (N = 505) and statin treatment-tolerant controls (N = 2047) were recruited from multiple sites in North America and Europe. SRM 3-5 was defined as symptoms consistent with muscle injury and an elevated creatine phosphokinase level >4 times upper limit of normal without another likely cause of muscle injury. Whole-exome sequencing and variant calling was coordinated from two analysis centres, and results of single-variant and gene-based burden tests were meta-analysed. No genome-wide significant associations were identified. Given the large number of cases, we had 80% power to identify a variant with minor allele frequency of 0.01 that increases the risk of SRM 6-fold at genome-wide significance. CONCLUSIONS: In this large whole-exome sequencing study of severe statin-related muscle injury conducted to date, we did not find evidence that rare coding variants are responsible for this adverse drug reaction. Larger sample sizes would be required to identify rare variants with small effects, but it is unclear whether such findings would be clinically actionable.

PTCD1 Is Required for Mitochondrial Oxidative-Phosphorylation: Possible Genetic Association with Alzheimer's Disease. - Fleck, Daniel; Phu, Lilian; Verschueren, Erik; Hinkle, Trent; Reichelt, Mike; Bhangale, Tushar; Haley, Benjamin; Wang, Yuanyuan; Graham, Robert; Kirkpatrick, Donald S; Sheng, Morgan; Bingol, Baris (J Neurosci, 2019)
In addition to amyloid-β plaques and tau tangles, mitochondrial dysfunction is implicated in the pathology of Alzheimer's disease (AD). Neurons heavily rely on mitochondrial function, and deficits in brain energy metabolism are detected early in AD; however, direct human genetic evidence for mitochondrial involvement in AD pathogenesis is limited. We analyzed whole-exome sequencing data of 4549 AD cases and 3332 age-matched controls and discovered that rare protein altering variants in the gene pentatricopeptide repeat-containing protein 1 () show a trend for enrichment in cases compared with controls. We show here that PTCD1 is required for normal mitochondrial rRNA levels, proper assembly of the mitochondrial ribosome and hence for mitochondrial translation and assembly of the electron transport chain. Loss of PTCD1 function impairs oxidative phosphorylation and forces cells to rely on glycolysis for energy production. Cells expressing the AD-linked variant of PTCD1 fail to sustain energy production under increased metabolic stress. In neurons, reduced PTCD1 expression leads to lower ATP levels and impacts spontaneous synaptic activity. Thus, our study uncovers a possible link between a protein required for mitochondrial function and energy metabolism and AD risk. Mitochondria are the main source of cellular energy and mitochondrial dysfunction is implicated in the pathology of Alzheimer's disease (AD) and other neurodegenerative disorders. Here, we identify a variant in the gene that is enriched in AD patients and demonstrate that PTCD1 is required for ATP generation through oxidative phosphorylation. PTCD1 regulates the level of 16S rRNA, the backbone of the mitoribosome, and is essential for mitochondrial translation and assembly of the electron transport chain. Cells expressing the AD-associated variant fail to maintain adequate ATP production during metabolic stress, and reduced PTCD1 activity disrupts neuronal energy homeostasis and dampens spontaneous transmission. Our work provides a mechanistic link between a protein required for mitochondrial function and genetic AD risk.

{Quality of dietary fat and genetic risk of type 2 diabetes: individual participant data meta-analysis - Merino, J.; Guasch-Ferr?, M.; Ellervik, C.; Dashti, H. S.; Sharp, S. J.; Wu, P.; Overvad, K.; Sarnowski, C.; Kuokkanen, M.; Lemaitre, R. N.; Justice, A. E.; Ericson, U.; et al. (BMJ, 2019)
{To investigate whether the genetic burden of type 2 diabetes modifies the association between the quality of dietary fat and the incidence of type 2 diabetes.\ Individual participant data meta-analysis.\ Eligible prospective cohort studies were systematically sourced from studies published between January 1970 and February 2017 through electronic searches in major medical databases (Medline, Embase, and Scopus) and discussion with investigators.\ Data from cohort studies or multicohort consortia with available genome-wide genetic data and information about the quality of dietary fat and the incidence of type 2 diabetes in participants of European descent was sought. Prospective cohorts that had accrued five or more years of follow-up were included. The type 2 diabetes genetic risk profile was characterized by a 68-variant polygenic risk score weighted by published effect sizes. Diet was recorded by using validated cohort-specific dietary assessment tools. Outcome measures were summary adjusted hazard ratios of incident type 2 diabetes for polygenic risk score, isocaloric replacement of carbohydrate (refined starch and sugars) with types of fat, and the interaction of types of fat with polygenic risk score.\ Of 102 305 participants from 15 prospective cohort studies, 20 015 type 2 diabetes cases were documented after a median follow-up of 12 years (interquartile range 9.4-14.2). The hazard ratio of type 2 diabetes per increment of 10 risk alleles in the polygenic risk score was 1.64 (95% confidence interval 1.54 to 1.75

{Relationship of Estimated GFR and Albuminuria to Concurrent Laboratory Abnormalities: An Individual Participant Data Meta-analysis in a Global Consortium - Inker, L. A.; Grams, M. E.; Levey, A. S.; Coresh, J.; Cirillo, M.; Collins, J. F.; Gansevoort, R. T.; Gutierrez, O. M.; Hamano, T.; Heine, G. H.; Ishikawa, S.; Jee, S. H.; et al. (Am J Kidney Dis, 2019)
Chronic kidney disease (CKD) is complicated by abnormalities that reflect disruption in filtration, tubular, and endocrine functions of the kidney. Our aim was to explore the relationship of specific laboratory result abnormalities and hypertension with the estimated glomerular filtration rate (eGFR) and albuminuria CKD staging framework.\ Cross-sectional individual participant-level analyses in a global consortium.\ 17 CKD and 38 general population and high-risk cohorts.\ Cohorts in the CKD Prognosis Consortium with data for eGFR and albuminuria, as well as a measurement of hemoglobin, bicarbonate, phosphorus, parathyroid hormone, potassium, or calcium, or hypertension.\ Data were obtained and analyzed between July 2015 and January 2018.\ We modeled the association of eGFR and albuminuria with hemoglobin, bicarbonate, phosphorus, parathyroid hormone, potassium, and calcium values using linear regression and with hypertension and categorical definitions of each abnormality using logistic regression. Results were pooled using random-effects meta-analyses.\ The CKD cohorts (n=254,666 participants) were 27% women and 10% black, with a mean age of 69 (SD, 12) years. The general population/high-risk cohorts (n=1,758,334) were 50% women and 2% black, with a mean age of 50 (16) years. There was a strong graded association between lower eGFR and all laboratory result abnormalities (ORs ranging from 3.27 [95% CI, 2.68-3.97] to 8.91 [95% CI, 7.22-10.99] comparing eGFRs of 15 to 29 with eGFRs of 45 to 59mL/min/1.73m2), whereas albuminuria had equivocal or weak associations with abnormalities (ORs ranging from 0.77 [95% CI, 0.60-0.99] to 1.92 [95% CI, 1.65-2.24] comparing urinary albumin-creatinine ratio > 300 vs < 30mg/g).\ Variations in study era, health care delivery system, typical diet, and laboratory assays.\ Lower eGFR was strongly associated with higher odds of multiple laboratory result abnormalities. Knowledge of risk associations might help guide management in the heterogeneous group of patients with CKD.

The role of functional status on the relationship between blood pressure and cognitive decline: the Cardiovascular Health Study. - Miller, Lindsay M; Peralta, Carmen A; Fitzpatrick, Annette L; Wu, Chenkai; Psaty, Bruce M; Newman, Anne B; Odden, Michelle C (J Hypertens, 2019)
OBJECTIVE: To examine whether self-reported functional status modified the association between blood pressure (BP) and cognitive decline among older adults. METHODS: The study included 2097 US adults aged 75 years and older from the Cardiovascular Health Study, followed for up to 6 years. Functional status was ascertained by self-reported limitation in activities of daily living (ADL; none vs. any). Cognitive function was assessed by the Modified Mini Mental State Exam (3MSE). We used linear mixed models to examine whether the presence of at least one ADL limitation modified the association between BP and cognitive decline. Potential confounders included demographics, physiologic measures, antihypertensive medication use and apolipoprotein E ε4 allele. We conducted stratified analyses for significant interactions between BP and ADL. RESULTS: The association between BP and change in 3MSE differed by baseline ADL limitation. Among participants without ADL limitation, elevated systolic BP (≥140 mmHg) was associated with a 0.15 decrease (95% CI -0.24 to -0.07); P value for interaction less than 0.001, whereas in those with an ADL limitation, elevated systolic BP was independently associated with a 0.30 increase in 3MSE scores per year (95% CI 0.06-0.55). Elevated diastolic BP (≥80 mmHg) was associated with an increase in cognitive function in both groups, although the increase was greater in those with ADL limitation (0.47 points per year vs. 0.18 points per year, P value for interaction = 0.01). CONCLUSION: Elevated BP appears to be associated with a decrease in cognitive scores among functioning older adults, and modest improvements in cognitive function among poorly functioning elders.

Sequencing Analysis at 8p23 Identifies Multiple Rare Variants in DLC1 Associated with Sleep-Related Oxyhemoglobin Saturation Level. - Liang, Jingjing; Cade, Brian E; He, Karen Y; Wang, Heming; Lee, Jiwon; Sofer, Tamar; Williams, Stephanie; Li, Ruitong; Chen, Han; Gottlieb, Daniel J; Evans, Daniel S; Guo, Xiuqing; et al. (Am J Hum Genet, 2019)
Average arterial oxyhemoglobin saturation during sleep (AvSpOS) is a clinically relevant measure of physiological stress associated with sleep-disordered breathing, and this measure predicts incident cardiovascular disease and mortality. Using high-depth whole-genome sequencing data from the National Heart, Lung, and Blood Institute (NHLBI) Trans-Omics for Precision Medicine (TOPMed) project and focusing on genes with linkage evidence on chromosome 8p23, we observed that six coding and 51 noncoding variants in a gene that encodes the GTPase-activating protein (DLC1) are significantly associated with AvSpOS and replicated in independent subjects. The combined DLC1 association evidence of discovery and replication cohorts reaches genome-wide significance in European Americans (p = 7.9 × 10). A risk score for these variants, built on an independent dataset, explains 0.97% of the AvSpOS variation and contributes to the linkage evidence. The 51 noncoding variants are enriched in regulatory features in a human lung fibroblast cell line and contribute to DLC1 expression variation. Mendelian randomization analysis using these variants indicates a significant causal effect of DLC1 expression in fibroblasts on AvSpOS. Multiple sources of information, including genetic variants, gene expression, and methylation, consistently suggest that DLC1 is a gene associated with AvSpOS.

Statin-induced LDL cholesterol response and type 2 diabetes: a bidirectional two-sample Mendelian randomization study. - Smit, Roelof A J; Trompet, Stella; Leong, Aaron; Goodarzi, Mark O; Postmus, Iris; Warren, Helen; Theusch, Elizabeth; Barnes, Michael R; Arsenault, Benoit J; Li, Xiaohui; Feng, QiPing; Chasman, Daniel I; et al. (Pharmacogenomics J, 2019)
It remains unclear whether the increased risk of new-onset type 2 diabetes (T2D) seen in statin users is due to low LDL-C concentrations, or due to the statin-induced proportional change in LDL-C. In addition, genetic instruments have not been proposed before to examine whether liability to T2D might cause greater proportional statin-induced LDL-C lowering. Using summary-level statistics from the Genomic Investigation of Statin Therapy (GIST, n = 40,914) and DIAGRAM (n = 159,208) consortia, we found a positive genetic correlation between LDL-C statin response and T2D using LD score regression (r = 0.36, s.e. = 0.13). However, mendelian randomization analyses did not provide support for statin response having a causal effect on T2D risk (OR 1.00 (95% CI: 0.97, 1.03) per 10% increase in statin response), nor that liability to T2D has a causal effect on statin-induced LDL-C response (0.20% increase in response (95% CI: -0.40, 0.80) per doubling of odds of liability to T2D). Although we found no evidence to suggest that proportional statin response influences T2D risk, a definitive assessment should be made in populations comprised exclusively of statin users, as the presence of nonstatin users in the DIAGRAM dataset may have substantially diluted our effect estimate.

Target genes, variants, tissues and transcriptional pathways influencing human serum urate levels. - Tin, Adrienne; Marten, Jonathan; Halperin Kuhns, Victoria L; Li, Yong; Wuttke, Matthias; Kirsten, Holger; Sieber, Karsten B; Qiu, Chengxiang; Gorski, Mathias; Yu, Zhi; Giri, Ayush; Sveinbjornsson, Gardar; et al. (Nat Genet, 2019)
Elevated serum urate levels cause gout and correlate with cardiometabolic diseases via poorly understood mechanisms. We performed a trans-ancestry genome-wide association study of serum urate in 457,690 individuals, identifying 183 loci (147 previously unknown) that improve the prediction of gout in an independent cohort of 334,880 individuals. Serum urate showed significant genetic correlations with many cardiometabolic traits, with genetic causality analyses supporting a substantial role for pleiotropy. Enrichment analysis, fine-mapping of urate-associated loci and colocalization with gene expression in 47 tissues implicated the kidney and liver as the main target organs and prioritized potentially causal genes and variants, including the transcriptional master regulators in the liver and kidney, HNF1A and HNF4A. Experimental validation showed that HNF4A transactivated the promoter of ABCG2, encoding a major urate transporter, in kidney cells, and that HNF4A p.Thr139Ile is a functional variant. Transcriptional coregulation within and across organs may be a general mechanism underlying the observed pleiotropy between urate and cardiometabolic traits.

Trans-ethnic association study of blood pressure determinants in over 750,000 individuals. - Giri, Ayush; Hellwege, Jacklyn N; Keaton, Jacob M; Park, Jihwan; Qiu, Chengxiang; Warren, Helen R; Torstenson, Eric S; Kovesdy, Csaba P; Sun, Yan V; Wilson, Otis D; Robinson-Cohen, Cassianne; Roumie, Christianne L; et al. (Nat Genet, 2019)
In this trans-ethnic multi-omic study, we reinterpret the genetic architecture of blood pressure to identify genes, tissues, phenomes and medication contexts of blood pressure homeostasis. We discovered 208 novel common blood pressure SNPs and 53 rare variants in genome-wide association studies of systolic, diastolic and pulse pressure in up to 776,078 participants from the Million Veteran Program (MVP) and collaborating studies, with analysis of the blood pressure clinical phenome in MVP. Our transcriptome-wide association study detected 4,043 blood pressure associations with genetically predicted gene expression of 840 genes in 45 tissues, and mouse renal single-cell RNA sequencing identified upregulated blood pressure genes in kidney tubule cells.

Trends in Blood Pressure and High-Sensitivity Cardiac Troponin-T with Cardiovascular Disease: The Cardiovascular Health Study. - Tehrani, David M; Fan, Wenjun; Nambi, Vijay; Gardin, Julius; Hirsch, Calvin H; Amsterdam, Ezra; deFilippi, Christopher R; Polonsky, Tamar; Wong, Nathan D (Am J Hypertens, 2019)
BACKGROUND: High-sensitivity cardiac troponin T (hs-cTnT) is individually associated with incident hypertension (HTN) and cardiovascular disease (CVD) events. We hypothesize that the increases in hs-cTnT with increases in blood pressure will be related to higher incidence of CVD. METHODS: The Cardiovascular Health Study is a longitudinal cohort of older adults. Those with hs-cTnT data and CVD risk factors at baseline and follow-up (2-3 years later) were stratified based on systolic blood pressure (SBP) (optimal: <120 mmHg, intermediate: 120-139 mmHg, elevated: ≥140 mmHg) and hs-cTnT (undetectable: <5 ng/L, detectable: 5-13 ng/L, elevated: ≥14 ng/L) categories. SBP and hs-cTnT were classified as increased or decreased if they changed categories between exams, and stable if they did not. Cox regression evaluated incident CVD events over an average 9 year follow-up. RESULTS: Among 2219 adults, 510 (23.0 %) had decreased hs-cTnT, 1,279 (57.6 %) had stable hs-cTnT, and 430 (19.4 %) had increased hs-cTnT. Those with increased hs-cTnT had a higher CVD risk with stable SBP (HR: 1.28 [1.04-1.57], p=0.02) or decreased SBP (HR: 1.57 [1.08-2.28], p=0.02) compared to those within the same SBP group but a stable hs-cTnT. In those with lower SBP at follow-up, there was an inverse relation between DBP and risk of CVD events in those with increased hs-cTnT (HR: 0.44 per 10 mmHg increase, p<0.01). CONCLUSION: An increase in hs-cTnT over time is associated with a higher risk of CVD even when the blood pressure is stable or decreases over time.

{Variants Associated with the Ankle Brachial Index Differ by Hispanic/Latino Ethnic Group: a genome-wide association study in the Hispanic Community Health Study/Study of Latinos - Sofer, T.; Emery, L.; Jain, D.; Ellis, A. M.; Laurie, C. C.; Allison, M. A.; Lee, J.; Kurniansyah, N.; Kerr, K. F.; Gonz?lez, H. M.; Tarraf, W.; Criqui, M. H.; et al. (Sci Rep, 2019)
Lower extremity peripheral artery disease (PAD) burden differs by race/ethnicity. Although familial aggregation and heritability studies suggest a genetic basis, little is known about the genetic susceptibility to PAD, especially in non-European descent populations. Genome-wide association studies (GWAS) of the ankle brachial index (ABI) and PAD (defined as an ABI < 0.90) have not been conducted in Hispanics/Latinos. We performed a GWAS of PAD and the ABI in 7,589 participants aged >45 years from the Hispanic Community Health Study/Study of Latinos (HCHS/SOL). We also performed GWAS for ABI stratified by Hispanic/Latino ethnic subgroups: Central American, Mexican, and South American (Mainland group), and Cuban, Dominican, and Puerto Rican (Caribbean group). We detected two genome-wide significant associations for the ABI in COMMD10 in Puerto Ricans, and at SYBU in the Caribbean group. The lead SNP rs4466200 in the COMMD10 gene had a replication p = 0.02 for the ABI in Multi-Ethnic Study of Atherosclerosis (MESA) African Americans, but it did not replicate in African Americans from the Cardiovascular Health Study (CHS). In a regional look-up, a nearby SNP rs12520838 had Bonferroni adjusted p = 0.05 (unadjusted p = 7.5 Ã— 10-5) for PAD in MESA Hispanics. Among three suggestive associations (p < 10-7) in subgroup-specific analyses, DMD on chromosome X, identified in Central Americans, replicated in MESA Hispanics (p = 2.2 Ã— 10-4). None of the previously reported ABI and PAD associations in whites generalized to Hispanics/Latinos.

Alzheimer Disease Pathology-Associated Polymorphism in a Complex Variable Number of Tandem Repeat Region Within the MUC6 Gene, Near the AP2A2 Gene. - Katsumata, Yuriko; Fardo, David W; Bachstetter, Adam D; Artiushin, Sergey C; Wang, Wang-Xia; Wei, Angela; Brzezinski, Lena J; Nelson, Bela G; Huang, Qingwei; Abner, Erin L; Anderson, Sonya; Patel, Indumati; et al. (J Neuropathol Exp Neurol, 2020)
We found evidence of late-onset Alzheimer disease (LOAD)-associated genetic polymorphism within an exon of Mucin 6 (MUC6) and immediately downstream from another gene: Adaptor Related Protein Complex 2 Subunit Alpha 2 (AP2A2). PCR analyses on genomic DNA samples confirmed that the size of the MUC6 variable number tandem repeat (VNTR) region was highly polymorphic. In a cohort of autopsied subjects with quantitative digital pathology data (n = 119), the size of the polymorphic region was associated with the severity of pTau pathology in neocortex. In a separate replication cohort of autopsied subjects (n = 173), more pTau pathology was again observed in subjects with longer VNTR regions (p = 0.031). Unlike MUC6, AP2A2 is highly expressed in human brain. AP2A2 expression was lower in a subset analysis of brain samples from persons with longer versus shorter VNTR regions (p = 0.014 normalizing with AP2B1 expression). Double-label immunofluorescence studies showed that AP2A2 protein often colocalized with neurofibrillary tangles in LOAD but was not colocalized with pTau proteinopathy in progressive supranuclear palsy, or with TDP-43 proteinopathy. In summary, polymorphism in a repeat-rich region near AP2A2 was associated with neocortical pTau proteinopathy (because of the unique repeats, prior genome-wide association studies were probably unable to detect this association), and AP2A2 was often colocalized with neurofibrillary tangles in LOAD.
Keywords: Adaptor Protein Complex 2; Adaptor Protein Complex alpha Subunits; Aged; Aged, 80 and over; Alzheimer Disease; Autopsy; Cohort Studies; Female; Genome-Wide Association Study; Genotype; Humans; Male; Minisatellite Repeats; Mucin-6; Neurofibrillary Tangles; Polymorphism, Genetic; Polymorphism, Single Nucleotide; TDP-43 Proteinopathies

{Androgens In Men Study (AIMS): protocol for meta-analyses of individual participant data investigating associations of androgens with health outcomes in men - Yeap, B. B.; Marriott, R. J.; Adams, R. J.; Antonio, L.; Ballantyne, C. M.; Bhasin, S.; Cawthon, P. M.; Couper, D. J.; Dobs, A. S.; Flicker, L.; Karlsson, M.; Martin, S. A.; et al. (BMJ Open, 2020)
This study aims to clarify the role(s) of endogenous sex hormones to influence health outcomes in men, specifically to define the associations of plasma testosterone with incidence of cardiovascular events, cancer, dementia and mortality risk, and to identify factors predicting testosterone concentrations. Data will be accrued from at least three Australian, two European and four North American population-based cohorts involving approximately 20 000 men.\ Eligible studies include prospective cohort studies with baseline testosterone concentrations measured using mass spectrometry and 5 years of follow-up data on incident cardiovascular events, mortality, cancer diagnoses or deaths, new-onset dementia or decline in cognitive function recorded. Data for men, who were not taking androgens or drugs suppressing testosterone production, metabolism or action; and had no prior orchidectomy, are eligible. Systematic literature searches were conducted from 14 June 2019 to 31 December 2019, with no date range set for searches. Aggregate level data will be sought where individual participant data (IPD) are not available. One-stage IPD random-effects meta-analyses will be performed, using linear mixed models, generalised linear mixed models and either stratified or frailty-augmented Cox regression models. Heterogeneity in estimates from different studies will be quantified and bias investigated using funnel plots. Effect size estimates will be presented in forest plots and non-negligible heterogeneity and bias investigated using subgroup or meta-regression analyses.\ Ethics approvals obtained for each of the participating cohorts state that participants have consented to have their data collected and used for research purposes. The Androgens In Men Study has been assessed as exempt from ethics review by the Human Ethics office at the University of Western Australia (file reference number RA/4/20/5014). Each of the component studies had obtained ethics approvals; please refer to respective component studies for details. Research findings will be disseminated to the scientific and broader community via the publication of four research articles, with each involving a separate set of IPD meta-analyses (articles will investigate different, distinct outcomes), at scientific conferences and meetings of relevant professional societies. Collaborating cohort studies will disseminate findings to study participants and local communities.\ CRD42019139668.

Association Between Blood Pressure and Later-Life Cognition Among Black and White Individuals. - Levine, Deborah A; Gross, Alden L; Briceño, Emily M; Tilton, Nicholas; Kabeto, Mohammed U; Hingtgen, Stephanie M; Giordani, Bruno J; Sussman, Jeremy B; Hayward, Rodney A; Burke, James F; Elkind, Mitchell S V; Manly, Jennifer J; et al. (JAMA Neurol, 2020)
Importance: Black individuals are more likely than white individuals to develop dementia. Whether higher blood pressure (BP) levels in black individuals explain differences between black and white individuals in dementia risk is uncertain. Objective: To determine whether cumulative BP levels explain racial differences in cognitive decline. Design, Setting, and Participants: Individual participant data from 5 cohorts (January 1971 to December 2017) were pooled from the Atherosclerosis Risk in Communities Study, Coronary Artery Risk Development in Young Adults Study, Cardiovascular Health Study, Framingham Offspring Study, and Northern Manhattan Study. Outcomes were standardized as t scores (mean [SD], 50 [10]); a 1-point difference represented a 0.1-SD difference in cognition. The median (interquartile range) follow-up was 12.4 (5.9-21.0) years. Analysis began September 2018. Main Outcomes and Measures: The primary outcome was change in global cognition, and secondary outcomes were change in memory and executive function. Exposures: Race (black vs white). Results: Among 34 349 participants, 19 378 individuals who were free of stroke and dementia and had longitudinal BP, cognitive, and covariate data were included in the analysis. The mean (SD) age at first cognitive assessment was 59.8 (10.4) years and ranged from 5 to 95 years. Of 19 378 individuals, 10 724 (55.3%) were female and 15 526 (80.1%) were white. Compared with white individuals, black individuals had significantly faster declines in global cognition (-0.03 points per year faster [95% CI, -0.05 to -0.01]; P = .004) and memory (-0.08 points per year faster [95% CI, -0.11 to -0.06]; P < .001) but significantly slower declines in executive function (0.09 points per year slower [95% CI, 0.08-0.10]; P < .001). Time-dependent cumulative mean systolic BP level was associated with significantly faster declines in global cognition (-0.018 points per year faster per each 10-mm Hg increase [95% CI, -0.023 to -0.014]; P < .001), memory (-0.028 points per year faster per each 10-mm Hg increase [95% CI, -0.035 to -0.021]; P < .001), and executive function (-0.01 points per year faster per each 10-mm Hg increase [95% CI, -0.014 to -0.007]; P < .001). After adjusting for cumulative mean systolic BP, differences between black and white individuals in cognitive slopes were attenuated for global cognition (-0.01 points per year [95% CI, -0.03 to 0.01]; P = .56) and memory (-0.06 points per year [95% CI, -0.08 to -0.03]; P < .001) but not executive function (0.10 points per year [95% CI, 0.09-0.11]; P < .001). Conclusions and Relevance: These results suggest that black individuals' higher cumulative BP levels may contribute to racial differences in later-life cognitive decline.

Association of Genetic Variation With Keratoconus. - McComish, Bennet J; Sahebjada, Srujana; Bykhovskaya, Yelena; Willoughby, Colin E; Richardson, Andrea J; Tenen, Abi; Charlesworth, Jac C; Macgregor, Stuart; Mitchell, Paul; Lucas, Sionne E M; Mills, Richard A; Mackey, David A; et al. (JAMA Ophthalmol, 2020)
Importance: Keratoconus is a condition in which the cornea progressively thins and protrudes in a conical shape, severely affecting refraction and vision. It is a major indication for corneal transplant. To discover new genetic loci associated with keratoconus and better understand the causative mechanism of this disease, we performed a genome-wide association study on patients with keratoconus. Objective: To identify genetic susceptibility regions for keratoconus in the human genome. Design, Setting, and Participants: This study was conducted with data from eye clinics in Australia, the United States, and Northern Ireland. The discovery cohort of individuals with keratoconus and control participants from Australia was genotyped using the Illumina HumanCoreExome single-nucleotide polymorphism array. After quality control and data cleaning, genotypes were imputed against the 1000 Genomes Project reference panel (phase III; version 5), and association analyses were completed using PLINK version 1.90. Single-nucleotide polymorphisms with P < 1.00 × 10-6 were assessed for replication in 3 additional cohorts. Control participants were drawn from the cohorts of the Blue Mountains Eye Study and a previous study of glaucoma. Replication cohorts were from a previous keratoconus genome-wide association study data set from the United States, a cohort of affected and control participants from Australia and Northern Ireland, and a case-control cohort from Victoria, Australia. Data were collected from January 2006 to March 2019. Main Outcomes and Measures: Associations between keratoconus and 6 252 612 genetic variants were estimated using logistic regression after adjusting for ancestry using the first 3 principal components. Results: The discovery cohort included 522 affected individuals and 655 control participants, while the replication cohorts included 818 affected individuals (222 from the United States, 331 from Australia and Northern Ireland, and 265 from Victoria, Australia) and 3858 control participants (2927 from the United States, 229 from Australia and Northern Ireland, and 702 from Victoria, Australia). Two novel loci reached genome-wide significance (defined as P < 5.00 × 10-8), with a P value of 7.46 × 10-9 at rs61876744 in patatin-like phospholipase domain-containing 2 gene (PNPLA2) on chromosome 11 and a P value of 6.35 × 10-12 at rs138380, 2.2 kb upstream of casein kinase I isoform epsilon gene (CSNK1E) on chromosome 22. One additional locus was identified with a P value less than 1.00 × 10-6 in mastermind-like transcriptional coactivator 2 (MAML2) on chromosome 11 (P = 3.91 × 10-7). The novel locus in PNPLA2 reached genome-wide significance in an analysis of all 4 cohorts (P = 2.45 × 10-8). Conclusions and Relevance: In this relatively large keratoconus genome-wide association study, we identified a genome-wide significant locus for keratoconus in the region of PNPLA2 on chromosome 11.
Keywords: Adult; Female; Fuchs' Endothelial Dystrophy; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Keratoconus; Lipase; Logistic Models; Male; Middle Aged; Polymorphism, Single Nucleotide

Association of Nonobstructive Chronic Bronchitis With Respiratory Health Outcomes in Adults. - Balte, Pallavi P; Chaves, Paulo H M; Couper, David J; Enright, Paul; Jacobs, David R; Kalhan, Ravi; Kronmal, Richard A; Loehr, Laura R; London, Stephanie J; Newman, Anne B; O'Connor, George T; Schwartz, Joseph E; et al. (JAMA Intern Med, 2020)
Importance: Chronic bronchitis has been associated with cigarette smoking as well as with e-cigarette use among young adults, but the association of chronic bronchitis in persons without airflow obstruction or clinical asthma, described as nonobstructive chronic bronchitis, with respiratory health outcomes remains uncertain. Objective: To assess whether nonobstructive chronic bronchitis is associated with adverse respiratory health outcomes in adult ever smokers and never smokers. Design, Setting, and Participants: This prospective cohort study included 22 325 adults without initial airflow obstruction (defined as the ratio of forced expiratory volume in the first second [FEV1] to forced vital capacity [FVC] of <0.70) or clinical asthma at baseline. The National Heart, Lung, and Blood Institute (NHLBI) Pooled Cohorts Study harmonized and pooled data from 9 US general population-based cohorts. Thus present study is based on data from 5 of these cohorts. Participants were enrolled from August 1971 through May 2007 and were followed up through December 2018. Exposures: Nonobstructive chronic bronchitis was defined by questionnaire at baseline as both cough and phlegm for at least 3 months for at least 2 consecutive years. Main Outcomes and Measures: Lung function was measured by prebronchodilator spirometry. Hospitalizations and deaths due to chronic lower respiratory disease and respiratory disease-related mortality were defined by events adjudication and administrative criteria. Models were stratified by smoking status and adjusted for anthropometric, sociodemographic, and smoking-related factors. The comparison group was participants without nonobstructive chronic bronchitis. Results: Among 22 325 adults included in the analysis, mean (SD) age was 53.0 (16.3) years (range, 18.0-95.0 years), 58.2% were female, 65.9% were non-Hispanic white, and 49.6% were ever smokers. Among 11 082 ever smokers with 99 869 person-years of follow-up, participants with nonobstructive chronic bronchitis (300 [2.7%]) had accelerated decreases in FEV1 (4.1 mL/y; 95% CI, 2.1-6.1 mL/y) and FVC (4.7 mL/y; 95% CI, 2.2-7.2 mL/y), increased risks of chronic lower respiratory disease-related hospitalization or mortality (hazard ratio [HR], 2.2; 95% CI, 1.7-2.7), and greater respiratory disease-related (HR, 2.0; 95% CI, 1.1-3.8) and all-cause mortality (HR, 1.5; 95% CI, 1.3-1.8) compared with ever smokers without nonobstructive chronic bronchitis. Among 11 243 never smokers with 120 004 person-years of follow-up, participants with nonobstructive chronic bronchitis (151 [1.3%]) had greater rates of chronic lower respiratory disease-related hospitalization or mortality (HR, 3.1; 95% CI, 2.1-4.5) compared with never smokers without nonobstructive chronic bronchitis. Nonobstructive chronic bronchitis was not associated with FEV1:FVC decline or incident airflow obstruction. The presence of at least 1 of the component symptoms of nonobstructive chronic bronchitis (ie, chronic cough or phlegm), which was common in both ever smokers (11.0%) and never smokers (6.7%), was associated with adverse respiratory health outcomes. Conclusions and Relevance: The findings suggest that nonobstructive chronic bronchitis is associated with adverse respiratory health outcomes, particularly in ever smokers, and may be a high-risk phenotype suitable for risk stratification and targeted therapies.
Keywords: Adolescent; Adult; Aged; Aged, 80 and over; Asthma; Bronchitis, Chronic; Female; Humans; Lung; Male; Middle Aged; Prospective Studies; Respiratory Function Tests; Smokers; Smoking; Young Adult

Carotid Intima-Media Thickness and the Risk of Sudden Cardiac Death: The ARIC Study and the CHS. - Suzuki, Takeki; Wang, Wanmei; Wilsdon, Anthony; Butler, Kenneth R; Adabag, Selcuk; Griswold, Michael E; Nambi, Vijay; Rosamond, Wayne; Sotoodehnia, Nona; Mosley, Thomas H (J Am Heart Assoc, 2020)
Background Sudden cardiac death (SCD) is associated with severe coronary heart disease in the great majority of cases. Whether carotid intima-media thickness (C-IMT), a known surrogate marker of subclinical atherosclerosis, is associated with risk of SCD in a general population remains unknown. The objective of this study was to investigate the association between C-IMT and risk of SCD. Methods and Results We examined a total of 20 862 participants: 15 307 participants of the ARIC (Atherosclerosis Risk in Communities) study and 5555 participants of the CHS (Cardiovascular Health Study). C-IMT and common carotid artery intima-media thickness was measured at baseline by ultrasound. Presence of plaque was judged by trained readers. Over a median of 23.5 years of follow-up, 569 participants had SCD (1.81 cases per 1000 person-years) in the ARIC study. Mean C-IMT and common carotid artery intima-media thickness were associated with risk of SCD after adjustment for traditional risk factors and time-varying adjustors: hazard ratios (HRs) with 95% CIs for fourth versus first quartile were 1.64 (1.15-2.63) and 1.49 (1.05-2.11), respectively. In CHS, 302 participants developed SCD (4.64 cases per 1000 person-years) over 13.1 years. Maximum C-IMT was associated with risk of SCD after adjustment: HR (95% CI) for fourth versus first quartile was 1.75 (1.22-2.51). Presence of plaque was associated with 35% increased risk of SCD: HR (95% CI) of 1.37 (1.13-1.67) in the ARIC study and 1.32 (1.04-1.68) in CHS. Conclusions C-IMT was associated with risk of SCD in 2 biracial community-based cohorts. C-IMT may be used as a marker of SCD risk and potentially to initiate early therapeutic interventions to mitigate the risk.

{Cerebral small vessel disease genomics and its implications across the lifespan - Sargurupremraj, M.; Suzuki, H.; Jian, X.; Sarnowski, C.; Evans, T. E.; Bis, J. C.; Eiriksdottir, G.; Sakaue, S.; Terzikhan, N.; Habes, M.; Zhao, W.; Armstrong, N. J.; et al. (Nat Commun, 2020)
White matter hyperintensities (WMH) are the most common brain-imaging feature of cerebral small vessel disease (SVD), hypertension being the main known risk factor. Here, we identify 27 genome-wide loci for WMH-volume in a cohort of 50,970 older individuals, accounting for modification/confounding by hypertension. Aggregated WMH risk variants were associated with altered white matter integrity (p = 2.5Ã—10-7) in brain images from 1,738 young healthy adults, providing insight into the lifetime impact of SVD genetic risk. Mendelian randomization suggested causal association of increasing WMH-volume with stroke, Alzheimer-type dementia, and of increasing blood pressure (BP) with larger WMH-volume, notably also in persons without clinical hypertension. Transcriptome-wide colocalization analyses showed association of WMH-volume with expression of 39 genes, of which four encode known drug targets. Finally, we provide insight into BP-independent biological pathways underlying SVD and suggest potential for genetic stratification of high-risk individuals and for genetically-informed prioritization of drug targets for prevention trials.

Chronic obstructive pulmonary disease and related phenotypes: polygenic risk scores in population-based and case-control cohorts. - Moll, Matthew; Sakornsakolpat, Phuwanat; Shrine, Nick; Hobbs, Brian D; DeMeo, Dawn L; John, Catherine; Guyatt, Anna L; McGeachie, Michael J; Gharib, Sina A; Obeidat, Ma'en; Lahousse, Lies; Wijnant, Sara R A; et al. (Lancet Respir Med, 2020)
BACKGROUND: Genetic factors influence chronic obstructive pulmonary disease (COPD) risk, but the individual variants that have been identified have small effects. We hypothesised that a polygenic risk score using additional variants would predict COPD and associated phenotypes. METHODS: We constructed a polygenic risk score using a genome-wide association study of lung function (FEV and FEV/forced vital capacity [FVC]) from the UK Biobank and SpiroMeta. We tested this polygenic risk score in nine cohorts of multiple ethnicities for an association with moderate-to-severe COPD (defined as FEV/FVC <0·7 and FEV <80% of predicted). Associations were tested using logistic regression models, adjusting for age, sex, height, smoking pack-years, and principal components of genetic ancestry. We assessed predictive performance of models by area under the curve. In a subset of studies, we also studied quantitative and qualitative CT imaging phenotypes that reflect parenchymal and airway pathology, and patterns of reduced lung growth. FINDINGS: The polygenic risk score was associated with COPD in European (odds ratio [OR] per SD 1·81 [95% CI 1·74-1·88] and non-European (1·42 [1·34-1·51]) populations. Compared with the first decile, the tenth decile of the polygenic risk score was associated with COPD, with an OR of 7·99 (6·56-9·72) in European ancestry and 4·83 (3·45-6·77) in non-European ancestry cohorts. The polygenic risk score was superior to previously described genetic risk scores and, when combined with clinical risk factors (ie, age, sex, and smoking pack-years), showed improved prediction for COPD compared with a model comprising clinical risk factors alone (AUC 0·80 [0·79-0·81] vs 0·76 [0·75-0·76]). The polygenic risk score was associated with CT imaging phenotypes, including wall area percent, quantitative and qualitative measures of emphysema, local histogram emphysema patterns, and destructive emphysema subtypes. The polygenic risk score was associated with a reduced lung growth pattern. INTERPRETATION: A risk score comprised of genetic variants can identify a small subset of individuals at markedly increased risk for moderate-to-severe COPD, emphysema subtypes associated with cigarette smoking, and patterns of reduced lung growth. FUNDING: US National Institutes of Health, Wellcome Trust.
Keywords: Adult; Case-Control Studies; Cohort Studies; Female; Forced Expiratory Volume; Genome-Wide Association Study; Humans; Male; Middle Aged; Phenotype; Pulmonary Disease, Chronic Obstructive; Risk Factors; Vital Capacity

{Discovery of rare variants associated with blood pressure regulation through meta-analysis of 1.3 million individuals - Surendran, P.; Feofanova, E. V.; Lahrouchi, N.; Ntalla, I.; Karthikeyan, S.; Cook, J.; Chen, L.; Mifsud, B.; Yao, C.; Kraja, A. T.; Cartwright, J. H.; Hellwege, J. N.; et al. (Nat Genet, 2020)
Genetic studies of blood pressure (BP) to date have mainly analyzed common variants (minor allele frequency > 0.05). In a meta-analysis of up to 1.3 million participants, we discovered 106 new BP-associated genomic regions and 87 rare (minor allele frequency â‰¤ 0.01) variant BP associations (P < 5 Ã— 10-8), of which 32 were in new BP-associated loci and 55 were independent BP-associated single-nucleotide variants within known BP-associated regions. Average effects of rare variants (44% coding) were 8 times larger than common variant effects and indicate potential candidate causal genes at new and known loci (for example, GATA5 and PLCB3). BP-associated variants (including rare and common) were enriched in regions of active chromatin in fetal tissues, potentially linking fetal development with BP regulation in later life. Multivariable Mendelian randomization suggested possible inverse effects of elevated systolic and diastolic BP on large artery stroke. Our study demonstrates the utility of rare-variant analyses for identifying candidate genes and the results highlight potential therapeutic targets.

A Dyadic Growth Modeling Approach for Examining Associations Between Weight Gain and Lung Function Decline. - Cornelius, Talea; Schwartz, Joseph E; Balte, Pallavi; Bhatt, Surya P; Cassano, Patricia A; Currow, David; Jacobs, David R; Johnson, Miriam; Kalhan, Ravi; Kronmal, Richard; Loehr, Laura; O'Connor, George T; et al. (Am J Epidemiol, 2020)
The relationship between body weight and lung function is complex. Using a dyadic multilevel linear modeling approach, treating body mass index (BMI; weight (kg)/height (m)2) and lung function as paired, within-person outcomes, we tested the hypothesis that persons with more rapid increase in BMI exhibit more rapid decline in lung function, as measured by forced expiratory volume in 1 second (FEV1), forced vital capacity (FVC), and their ratio (FEV1:FVC). Models included random intercepts and slopes and adjusted for sociodemographic and smoking-related factors. A sample of 9,115 adults with paired measurements of BMI and lung function taken at ≥3 visits were selected from a pooled set of 5 US population-based cohort studies (1983-2018; mean age at baseline = 46 years; median follow-up, 19 years). At age 46 years, average annual rates of change in BMI, FEV1, FVC, and FEV1:FVC ratio were 0.22 kg/m2/year, -25.50 mL/year, -21.99 mL/year, and -0.24%/year, respectively. Persons with steeper BMI increases had faster declines in FEV1 (r = -0.16) and FVC (r = -0.26) and slower declines in FEV1:FVC ratio (r = 0.11) (all P values < 0.0001). Results were similar in subgroup analyses. Residual correlations were negative (P < 0.0001), suggesting additional interdependence between BMI and lung function. Results show that greater rates of weight gain are associated with greater rates of lung function loss.
Keywords: Adult; Aged; Body Mass Index; Cohort Studies; Humans; Linear Models; Lung; Middle Aged; Respiratory Function Tests; Weight Gain

{Dynamic incorporation of multiple in silico functional annotations empowers rare variant association analysis of large whole-genome sequencing studies at scale - Li, X.; Li, Z.; Zhou, H.; Gaynor, S. M.; Liu, Y.; Chen, H.; Sun, R.; Dey, R.; Arnett, D. K.; Aslibekyan, S.; Ballantyne, C. M.; Bielak, L. F.; et al. (Nat Genet, 2020)
Large-scale whole-genome sequencing studies have enabled the analysis of rare variants (RVs) associated with complex phenotypes. Commonly used RV association tests have limited scope to leverage variant functions. We propose STAAR (variant-set test for association using annotation information), a scalable and powerful RV association test method that effectively incorporates both variant categories and multiple complementary annotations using a dynamic weighting scheme. For the latter, we introduce 'annotation principal components', multidimensional summaries of in silico variant annotations. STAAR accounts for population structure and relatedness and is scalable for analyzing very large cohort and biobank whole-genome sequencing studies of continuous and dichotomous traits. We applied STAAR to identify RVs associated with four lipid traits in 12,316 discovery and 17,822 replication samples from the Trans-Omics for Precision Medicine Program. We discovered and replicated new RV associations, including disruptive missense RVs of NPC1L1 and an intergenic region near APOC1P1 associated with low-density lipoprotein cholesterol.

{Fatty acids in the de novo lipogenesis pathway and incidence of type 2 diabetes: A pooled analysis of prospective cohort studies - Imamura, F.; Fretts, A. M.; Marklund, M.; Ardisson Korat, A. V.; Yang, W. S.; Lankinen, M.; Qureshi, W.; Helmer, C.; Chen, T. A.; Virtanen, J. K.; Wong, K.; Bassett, J. K.; et al. (PLoS Med, 2020)
De novo lipogenesis (DNL) is the primary metabolic pathway synthesizing fatty acids from carbohydrates, protein, or alcohol. Our aim was to examine associations of in vivo levels of selected fatty acids (16:0, 16:1n7, 18:0, 18:1n9) in DNL with incidence of type 2 diabetes (T2D).\ Seventeen cohorts from 12 countries (7 from Europe, 7 from the United States, 1 from Australia, 1 from Taiwan; baseline years = 1970-1973 to 2006-2010) conducted harmonized individual-level analyses of associations of DNL-related fatty acids with incident T2D. In total, we evaluated 65,225 participants (mean ages = 52.3-75.5 years; % women = 20.4%-62.3% in 12 cohorts recruiting both sexes) and 15,383 incident cases of T2D over the 9-year follow-up on average. Cohort-specific association of each of 16:0, 16:1n7, 18:0, and 18:1n9 with incident T2D was estimated, adjusted for demographic factors, socioeconomic characteristics, alcohol, smoking, physical activity, dyslipidemia, hypertension, menopausal status, and adiposity. Cohort-specific associations were meta-analyzed with an inverse-variance-weighted approach. Each of the 4 fatty acids positively related to incident T2D. Relative risks (RRs) per cohort-specific range between midpoints of the top and bottom quintiles of fatty acid concentrations were 1.53 (1.41-1.66; p < 0.001) for 16:0, 1.40 (1.33-1.48; p < 0.001) for 16:1n-7, 1.14 (1.05-1.22; p = 0.001) for 18:0, and 1.16 (1.07-1.25; p < 0.001) for 18:1n9. Heterogeneity was seen across cohorts (I2 = 51.1%-73.1% for each fatty acid) but not explained by lipid fractions and global geographical regions. Further adjusted for triglycerides (and 16:0 when appropriate) to evaluate associations independent of overall DNL, the associations remained significant for 16:0, 16:1n7, and 18:0 but were attenuated for 18:1n9 (RR = 1.03, 95% confidence interval (CI) = 0.94-1.13). These findings had limitations in potential reverse causation and residual confounding by imprecisely measured or unmeasured factors.\ Concentrations of fatty acids in the DNL were positively associated with T2D incidence. Our findings support further work to investigate a possible role of DNL and individual fatty acids in the development of T2D.

Gene-educational attainment interactions in a multi-ancestry genome-wide meta-analysis identify novel blood pressure loci. - de Las Fuentes, Lisa; Sung, Yun Ju; Noordam, Raymond; Winkler, Thomas; Feitosa, Mary F; Schwander, Karen; Bentley, Amy R; Brown, Michael R; Guo, Xiuqing; Manning, Alisa; Chasman, Daniel I; Aschard, Hugues; et al. (Mol Psychiatry, 2020)
Educational attainment is widely used as a surrogate for socioeconomic status (SES). Low SES is a risk factor for hypertension and high blood pressure (BP). To identify novel BP loci, we performed multi-ancestry meta-analyses accounting for gene-educational attainment interactions using two variables, "Some College" (yes/no) and "Graduated College" (yes/no). Interactions were evaluated using both a 1 degree of freedom (DF) interaction term and a 2DF joint test of genetic and interaction effects. Analyses were performed for systolic BP, diastolic BP, mean arterial pressure, and pulse pressure. We pursued genome-wide interrogation in Stage 1 studies (N = 117 438) and follow-up on promising variants in Stage 2 studies (N = 293 787) in five ancestry groups. Through combined meta-analyses of Stages 1 and 2, we identified 84 known and 18 novel BP loci at genome-wide significance level (P < 5 × 10). Two novel loci were identified based on the 1DF test of interaction with educational attainment, while the remaining 16 loci were identified through the 2DF joint test of genetic and interaction effects. Ten novel loci were identified in individuals of African ancestry. Several novel loci show strong biological plausibility since they involve physiologic systems implicated in BP regulation. They include genes involved in the central nervous system-adrenal signaling axis (ZDHHC17, CADPS, PIK3C2G), vascular structure and function (GNB3, CDON), and renal function (HAS2 and HAS2-AS1, SLIT3). Collectively, these findings suggest a role of educational attainment or SES in further dissection of the genetic architecture of BP.

The genetic architecture of the human cerebral cortex - Grasby, Katrina L.; Jahanshad, Neda; Painter, Jodie N.; Colodro-Conde, Lucía; Bralten, Janita; Hibar, Derrek P.; Lind, Penelope A.; Pizzagalli, Fabrizio; Ching, Christopher R. K.; McMahon, Mary Agnes B.; Shatokhina, Natalia; Zsembik, Leo C. P.; et al. (Science, 2020)

{Genetic correlations and genome-wide associations of cortical structure in general population samples of 22,824 adults - Hofer, E.; Roshchupkin, G. V.; Adams, H. H. H.; Knol, M. J.; Lin, H.; Li, S.; Zare, H.; Ahmad, S.; Armstrong, N. J.; Satizabal, C. L.; Bernard, M.; Bis, J. C.; et al. (Nat Commun, 2020)
Cortical thickness, surface area and volumes vary with age and cognitive function, and in neurological and psychiatric diseases. Here we report heritability, genetic correlations and genome-wide associations of these cortical measures across the whole cortex, and in 34 anatomically predefined regions. Our discovery sample comprises 22,824 individuals from 20 cohorts within the Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) consortium and the UK Biobank. We identify genetic heterogeneity between cortical measures and brain regions, and 160 genome-wide significant associations pointing to wnt/Î²-catenin, TGF-Î² and sonic hedgehog pathways. There is enrichment for genes involved in anthropometric traits, hindbrain development, vascular and neurodegenerative disease and psychiatric conditions. These data are a rich resource for studies of the biological mechanisms behind cortical development and aging.

{Genetic Determinants of Electrocardiographic P-wave Duration and Relation to Atrial Fibrillation - Weng, L. C.; Hall, A. W.; Choi, S. H.; Jurgens, S. J.; Haessler, J.; Bihlmeyer, N. A.; Grarup, N.; Lin, H.; Teumer, A.; Li-Gao, R.; Yao, J.; Guo, X.; et al. (Circ Genom Precis Med, 2020)
Background - The P-wave duration (PWD) is an electrocardiographic (ECG) measurement that represents cardiac conduction in the atria. Shortened or prolonged PWD is associated with atrial fibrillation (AF). We used exome chip data to examine the associations between common and rare variants with PWD. Methods - Fifteen studies comprising 64,440 individuals (56,943 European, 5,681 African, 1,186 Hispanic, 630 Asian), and 230,000 variants were used to examine associations with maximum PWD across the 12-lead ECG. Meta-analyses summarized association results for common variants; gene-based burden and SKAT tests examined low-frequency variant-PWD associations. Additionally, we examined the associations between PWD loci and AF using previous AF GWAS. Results - We identified 21 common and low-frequency genetic loci (14 novel) associated with maximum PWD, including several AF loci (TTN, CAND2, SCN10A, PITX2, CAV1, SYNPO2L, SOX5, TBX5, MYH6, RPL3L). The top variants at known sarcomere genes (TTN, MYH6) were associated with longer PWD and increased AF risk. However, top variants at other loci (e.g., PITX2 and SCN10A) were associated with longer PWD but lower AF risk. Conclusions - Our results highlight multiple novel genetic loci associated with PWD, and underscore the shared mechanisms of atrial conduction and AF. Prolonged PWD may be an endophenotype for several different genetic mechanisms of AF.

Genetic loci associated with prevalent and incident myocardial infarction and coronary heart disease in the Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) Consortium. - Hahn, Julie; Fu, Yi-Ping; Brown, Michael R; Bis, Joshua C; de Vries, Paul S; Feitosa, Mary F; Yanek, Lisa R; Weiss, Stefan; Giulianini, Franco; Smith, Albert Vernon; Guo, Xiuqing; Bartz, Traci M; et al. (PLoS One, 2020)
BACKGROUND: Genome-wide association studies have identified multiple genomic loci associated with coronary artery disease, but most are common variants in non-coding regions that provide limited information on causal genes and etiology of the disease. To overcome the limited scope that common variants provide, we focused our investigation on low-frequency and rare sequence variations primarily residing in coding regions of the genome. METHODS AND RESULTS: Using samples of individuals of European ancestry from ten cohorts within the Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) consortium, both cross-sectional and prospective analyses were conducted to examine associations between genetic variants and myocardial infarction (MI), coronary heart disease (CHD), and all-cause mortality following these events. For prevalent events, a total of 27,349 participants of European ancestry, including 1831 prevalent MI cases and 2518 prevalent CHD cases were used. For incident cases, a total of 55,736 participants of European ancestry were included (3,031 incident MI cases and 5,425 incident CHD cases). There were 1,860 all-cause deaths among the 3,751 MI and CHD cases from six cohorts that contributed to the analysis of all-cause mortality. Single variant and gene-based analyses were performed separately in each cohort and then meta-analyzed for each outcome. A low-frequency intronic variant (rs988583) in PLCL1 was significantly associated with prevalent MI (OR = 1.80, 95% confidence interval: 1.43, 2.27; P = 7.12 × 10-7). We conducted gene-based burden tests for genes with a cumulative minor allele count (cMAC) ≥ 5 and variants with minor allele frequency (MAF) < 5%. TMPRSS5 and LDLRAD1 were significantly associated with prevalent MI and CHD, respectively, and RC3H2 and ANGPTL4 were significantly associated with incident MI and CHD, respectively. No loci were significantly associated with all-cause mortality following a MI or CHD event. CONCLUSION: This study identified one known locus (ANGPTL4) and four new loci (PLCL1, RC3H2, TMPRSS5, and LDLRAD1) associated with cardiovascular disease risk that warrant further investigation.
Keywords: Aging; Coronary Artery Disease; Cross-Sectional Studies; Europe; European Continental Ancestry Group; Genetic Loci; Genome-Wide Association Study; Humans; Myocardial Infarction; Polymorphism, Single Nucleotide; Prospective Studies

Genetic Studies of Leptin Concentrations Implicate Leptin in the Regulation of Early Adiposity. - Yaghootkar, Hanieh; Zhang, Yiying; Spracklen, Cassandra N; Karaderi, Tugce; Huang, Lam Opal; Bradfield, Jonathan; Schurmann, Claudia; Fine, Rebecca S; Preuss, Michael H; Kutalik, Zoltán; Wittemans, Laura Bl; Lu, Yingchang; et al. (Diabetes, 2020)
Leptin influences food intake by informing the brain about the status of body fat stores. Rare mutations associated with congenital leptin deficiency cause severe early-onset obesity that can be mitigated by administering leptin. However, the role of genetic regulation of leptin in polygenic obesity remains poorly understood. We performed an exome-based analysis in up to 57,232 individuals of diverse ancestries to identify genetic variants that influence adiposity-adjusted leptin concentrations. We identify five novel variants, including four missense variants, in , and , and one intergenic variant near The missense variant Val94Met (rs17151919) in was common in individuals of African ancestry only and its association with lower leptin concentrations was specific to this ancestry (P=2x10, n=3,901). Using analyses, we show that the Met94 allele decreases leptin secretion. We also show that the Met94 allele is associated with higher BMI in young African-ancestry children but not in adults, suggesting leptin regulates early adiposity.

{Genome-wide association and Mendelian randomisation analysis provide insights into the pathogenesis of heart failure - Shah, S.; Henry, A.; Roselli, C.; Lin, H.; Sveinbj?rnsson, G.; Fatemifar, G.; Hedman, ?. K.; Wilk, J. B.; Morley, M. P.; Chaffin, M. D.; Helgadottir, A.; Verweij, N.; et al. (Nat Commun, 2020)
Heart failure (HF) is a leading cause of morbidity and mortality worldwide. A small proportion of HF cases are attributable to monogenic cardiomyopathies and existing genome-wide association studies (GWAS) have yielded only limited insights, leaving the observed heritability of HF largely unexplained. We report results from a GWAS meta-analysis of HF comprising 47,309 cases and 930,014 controls. Twelve independent variants at 11 genomic loci are associated with HF, all of which demonstrate one or more associations with coronary artery disease (CAD), atrial fibrillation, or reduced left ventricular function, suggesting shared genetic aetiology. Functional analysis of non-CAD-associated loci implicate genes involved in cardiac development (MYOZ1, SYNPO2L), protein homoeostasis (BAG3), and cellular senescence (CDKN1A). Mendelian randomisation analysis supports causal roles for several HF risk factors, and demonstrates CAD-independent effects for atrial fibrillation, body mass index, and hypertension. These findings extend our knowledge of the pathways underlying HF and may inform new therapeutic strategies.

{Genome-Wide Association Study Meta-Analysis of Stroke in 22 000 Individuals of African Descent Identifies Novel Associations With Stroke - Keene, K. L.; Hyacinth, H. I.; Bis, J. C.; Kittner, S. J.; Mitchell, B. D.; Cheng, Y. C.; Pare, G.; Chong, M.; O'Donnell, M.; Meschia, J. F.; Chen, W. M.; Sale, M. M.; et al. (Stroke, 2020)
Stroke is a complex disease with multiple genetic and environmental risk factors. Blacks endure a nearly 2-fold greater risk of stroke and are 2× to 3× more likely to die from stroke than European Americans.\ The COMPASS (Consortium of Minority Population Genome-Wide Association Studies of Stroke) has conducted a genome-wide association meta-analysis of stroke in >22 000 individuals of African ancestry (3734 cases, 18 317 controls) from 13 cohorts.\ In meta-analyses, we identified one single nucleotide polymorphism (rs55931441) near the HNF1A gene that reached genome-wide significance (P=4.62×10-8) and an additional 29 variants with suggestive evidence of association (P<1×10-6), representing 24 unique loci. For validation, a look-up analysis for a 100 kb region flanking the COMPASS single nucleotide polymorphism was performed in SiGN (Stroke Genetics Network) Europeans, SiGN Hispanics, and METASTROKE (Europeans). Using a stringent Bonferroni correction P value of 2.08×10-3 (0.05/24 unique loci), we were able to validate associations at the HNF1A locus in both SiGN (P=8.18×10-4) and METASTROKE (P=1.72×10-3) European populations. Overall, 16 of 24 loci showed evidence for validation across multiple populations. Previous studies have reported associations between variants in the HNF1A gene and lipids, C-reactive protein, and risk of coronary artery disease and stroke. Suggestive associations with variants in the SFXN4 and TMEM108 genes represent potential novel ischemic stroke loci.\ These findings represent the most thorough investigation of genetic determinants of stroke in individuals of African descent, to date.

{An individual participant data analysis of prospective cohort studies on the association between subclinical thyroid dysfunction and depressive symptoms - Wildisen, L.; Del Giovane, C.; Moutzouri, E.; Beglinger, S.; Syrogiannouli, L.; Collet, T. H.; Cappola, A. R.; ?svold, B. O.; Bakker, S. J. L.; Yeap, B. B.; Almeida, O. P.; Ceresini, G.; et al. (Sci Rep, 2020)
{In subclinical hypothyroidism, the presence of depressive symptoms is often a reason for starting levothyroxine treatment. However, data are conflicting on the association between subclinical thyroid dysfunction and depressive symptoms. We aimed to examine the association between subclinical thyroid dysfunction and depressive symptoms in all prospective cohorts with relevant data available. We performed a systematic review of the literature from Medline, Embase, Cumulative Index to Nursing and Allied Health Literature, and the Cochrane Library from inception to 10th May 2019. We included prospective cohorts with data on thyroid status at baseline and depressive symptoms during follow-up. The primary outcome was depressive symptoms measured at first available follow-up, expressed on the Beck's Depression Inventory (BDI) scale (range 0-63, higher values indicate more depressive symptoms, minimal clinically important difference: 5 points). We performed a two-stage individual participant data (IPD) analysis comparing participants with subclinical hypo- or hyperthyroidism versus euthyroidism, adjusting for depressive symptoms at baseline, age, sex, education, and income (PROSPERO CRD42018091627). Six cohorts met the inclusion criteria, with IPD on 23,038 participants. Their mean age was 60 years, 65% were female, 21,025 were euthyroid, 1342 had subclinical hypothyroidism and 671 subclinical hyperthyroidism. At first available follow-up [mean 8.2 (Â± 4.3) years], BDI scores did not differ between participants with subclinical hypothyroidism (mean difference = 0.29, 95% confidence interval = - 0.17 to 0.76

Inherited causes of clonal haematopoiesis in 97,691 whole genomes. - Bick, Alexander G; Weinstock, Joshua S; Nandakumar, Satish K; Fulco, Charles P; Bao, Erik L; Zekavat, Seyedeh M; Szeto, Mindy D; Liao, Xiaotian; Leventhal, Matthew J; Nasser, Joseph; Chang, Kyle; Laurie, Cecelia; et al. (Nature, 2020)
Age is the dominant risk factor for most chronic human diseases, but the mechanisms through which ageing confers this risk are largely unknown. The age-related acquisition of somatic mutations that lead to clonal expansion in regenerating haematopoietic stem cell populations has recently been associated with both haematological cancer and coronary heart disease-this phenomenon is termed clonal haematopoiesis of indeterminate potential (CHIP). Simultaneous analyses of germline and somatic whole-genome sequences provide the opportunity to identify root causes of CHIP. Here we analyse high-coverage whole-genome sequences from 97,691 participants of diverse ancestries in the National Heart, Lung, and Blood Institute Trans-omics for Precision Medicine (TOPMed) programme, and identify 4,229 individuals with CHIP. We identify associations with blood cell, lipid and inflammatory traits that are specific to different CHIP driver genes. Association of a genome-wide set of germline genetic variants enabled the identification of three genetic loci associated with CHIP status, including one locus at TET2 that was specific to individuals of African ancestry. In silico-informed in vitro evaluation of the TET2 germline locus enabled the identification of a causal variant that disrupts a TET2 distal enhancer, resulting in increased self-renewal of haematopoietic stem cells. Overall, we observe that germline genetic variation shapes haematopoietic stem cell function, leading to CHIP through mechanisms that are specific to clonal haematopoiesis as well as shared mechanisms that lead to somatic mutations across tissues.

Level and change in N-terminal pro B-type Natriuretic Peptide and kidney function and survival to age 90. - Häberle, Astrid D; Biggs, Mary L; Cushman, Mary; Psaty, Bruce M; Newman, Anne B; Shlipak, Michael G; Gottdiener, John; Wu, Chenkai; Gardin, Julius M; Bansal, Nisha; Odden, Michelle C (J Gerontol A Biol Sci Med Sci, 2020)
BACKGROUND: Many traditional cardiovascular risk factors do not predict survival to very old age. Studies have shown associations of estimated glomerular filtration rate (eGFR) and N-terminal pro-B-type natriuretic peptide (NT-pro-BNP) with cardiovascular disease and mortality in older populations. This study aimed to evaluate the associations of the level and change in eGFR and NT-pro-BNP with longevity to age 90 years. METHODS: The population included participants (n=3,645) in the Cardiovascular Health Study, aged between 67-75 at baseline. The main exposures were eGFR, calculated with the Berlin Initiative Study equation (BIS2), and NT-pro-BNP, and the main outcome was survival to age 90. Mixed models were used to estimate level and change of the main exposures. RESULTS: There was an association between baseline level and change of both eGFR and NT-pro-BNP and survival to 90, and this association persisted after adjustment for covariates. Each 10 ml/min per 1.73 m2 higher eGFR level was associated with an adjusted odds ratio (OR) of 1.23 (95% CI: 1.13, 1.34) of survival to 90, and a 0.5 ml/min/ 1.73 m2 slower decline in eGFR was associated with an OR of 1.51 (95% CI: 1.31, 1.74). A 2-fold higher level of NT-pro-BNP level had an adjusted OR of 0.67 (95% CI: 0.61, 0.73), and a 1.05-fold increase per year in NT-pro-BNP had an OR of 0.53 (95% CI: 0.43, 0.65) for survival to age 90. CONCLUSION: eGFR and NT-pro-BNP appear to be important risk factors for longevity to age 90.

Lung function decline in former smokers and low-intensity current smokers: a secondary data analysis of the NHLBI Pooled Cohorts Study. - Oelsner, Elizabeth C; Balte, Pallavi P; Bhatt, Surya P; Cassano, Patricia A; Couper, David; Folsom, Aaron R; Freedman, Neal D; Jacobs, David R; Kalhan, Ravi; Mathew, Amanda R; Kronmal, Richard A; Loehr, Laura R; et al. (Lancet Respir Med, 2020)
BACKGROUND: Former smokers now outnumber current smokers in many developed countries, and current smokers are smoking fewer cigarettes per day. Some data suggest that lung function decline normalises with smoking cessation; however, mechanistic studies suggest that lung function decline could continue. We hypothesised that former smokers and low-intensity current smokers have accelerated lung function decline compared with never-smokers, including among those without prevalent lung disease. METHODS: We used data on six US population-based cohorts included in the NHLBI Pooled Cohort Study. We restricted the sample to participants with valid spirometry at two or more exams. Two cohorts recruited younger adults (≥17 years), two recruited middle-aged and older adults (≥45 years), and two recruited only elderly adults (≥65 years) with examinations done between 1983 and 2014. FEV decline in sustained former smokers and current smokers was compared to that of never-smokers by use of mixed models adjusted for sociodemographic and anthropometric factors. Differential FEV decline was also evaluated according to duration of smoking cessation and cumulative (number of pack-years) and current (number of cigarettes per day) cigarette consumption. FINDINGS: 25 352 participants (ages 17-93 years) completed 70 228 valid spirometry exams. Over a median follow-up of 7 years (IQR 3-20), FEV decline at the median age (57 years) was 31·01 mL per year (95% CI 30·66-31·37) in sustained never-smokers, 34·97 mL per year (34·36-35·57) in former smokers, and 39·92 mL per year (38·92-40·92) in current smokers. With adjustment, former smokers showed an accelerated FEV decline of 1·82 mL per year (95% CI 1·24-2·40) compared to never-smokers, which was approximately 20% of the effect estimate for current smokers (9·21 mL per year; 95% CI 8·35-10·08). Compared to never-smokers, accelerated FEV decline was observed in former smokers for decades after smoking cessation and in current smokers with low cumulative cigarette consumption (<10 pack-years). With respect to current cigarette consumption, the effect estimate for FEV decline in current smokers consuming less than five cigarettes per day (7·65 mL per year; 95% CI 6·21-9·09) was 68% of that in current smokers consuming 30 or more cigarettes per day (11·24 mL per year; 9·86-12·62), and around five times greater than in former smokers (1·57 mL per year; 1·00-2·14). Among participants without prevalent lung disease, associations were attenuated but were consistent with the main results. INTERPRETATION: Former smokers and low-intensity current smokers have accelerated lung function decline compared with never-smokers. These results suggest that all levels of smoking exposure are likely to be associated with lasting and progressive lung damage. FUNDING: National Institutes of Health, National Heart Lung and Blood Institute, and US Environmental Protection Agency.
Keywords: Adult; Aged; Case-Control Studies; Ex-Smokers; Female; Follow-Up Studies; Humans; Lung; Male; Middle Aged; National Heart, Lung, and Blood Institute (U.S.); Non-Smokers; Respiratory Physiological Phenomena; Smokers; Smoking; Spirometry; United States; Young Adult

Mendelian randomization analysis does not support causal associations of birth weight with hypertension risk and blood pressure in adulthood. - Zheng, Yan; Huang, Tao; Wang, Tiange; Mei, Zhendong; Sun, Zhonghan; Zhang, Tao; Ellervik, Christina; Chai, Jin-Fang; Sim, Xueling; van Dam, Rob M; Tai, E-Shyong; Koh, Woon-Puay; et al. (Eur J Epidemiol, 2020)
Epidemiology studies suggested that low birthweight was associated with a higher risk of hypertension in later life. However, little is known about the causality of such associations. In our study, we evaluated the causal association of low birthweight with adulthood hypertension following a standard analytic protocol using the study-level data of 183,433 participants from 60 studies (CHARGE-BIG consortium), as well as that with blood pressure using publicly available summary-level genome-wide association data from EGG consortium of 153,781 participants, ICBP consortium and UK Biobank cohort together of 757,601 participants. We used seven SNPs as the instrumental variable in the study-level analysis and 47 SNPs in the summary-level analysis. In the study-level analyses, decreased birthweight was associated with a higher risk of hypertension in adults (the odds ratio per 1 standard deviation (SD) lower birthweight, 1.22; 95% CI 1.16 to 1.28), while no association was found between genetically instrumented birthweight and hypertension risk (instrumental odds ratio for causal effect per 1 SD lower birthweight, 0.97; 95% CI 0.68 to 1.41). Such results were consistent with that from the summary-level analyses, where the genetically determined low birthweight was not associated with blood pressure measurements either. One SD lower genetically determined birthweight was not associated with systolic blood pressure (β = - 0.76, 95% CI - 2.45 to 1.08 mmHg), 0.06 mmHg lower diastolic blood pressure (β = - 0.06, 95% CI - 0.93 to 0.87 mmHg), or pulse pressure (β = - 0.65, 95% CI - 1.38 to 0.69 mmHg, all p > 0.05). Our findings suggest that the inverse association of birthweight with hypertension risk from observational studies was not supported by large Mendelian randomization analyses.

Meta-analysis uncovers genome-wide significant variants for rapid kidney function decline. - Gorski, Mathias; Jung, Bettina; Li, Yong; Matias-Garcia, Pamela R; Wuttke, Matthias; Coassin, Stefan; Thio, Chris H L; Kleber, Marcus E; Winkler, Thomas W; Wanner, Veronika; Chai, Jin-Fang; Chu, Audrey Y; et al. (Kidney Int, 2020)
Rapid decline of glomerular filtration rate estimated from creatinine (eGFRcrea) is associated with severe clinical endpoints. In contrast to cross-sectionally assessed eGFRcrea, the genetic basis for rapid eGFRcrea decline is largely unknown. To help define this, we meta-analyzed 42 genome-wide association studies from the Chronic Kidney Diseases Genetics Consortium and United Kingdom Biobank to identify genetic loci for rapid eGFRcrea decline. Two definitions of eGFRcrea decline were used: 3 mL/min/1.73m/year or more ("Rapid3"; encompassing 34,874 cases, 107,090 controls) and eGFRcrea decline 25% or more and eGFRcrea under 60 mL/min/1.73m at follow-up among those with eGFRcrea 60 mL/min/1.73m or more at baseline ("CKDi25"; encompassing 19,901 cases, 175,244 controls). Seven independent variants were identified across six loci for Rapid3 and/or CKDi25: consisting of five variants at four loci with genome-wide significance (near UMOD-PDILT (2), PRKAG2, WDR72, OR2S2) and two variants among 265 known eGFRcrea variants (near GATM, LARP4B). All these loci were novel for Rapid3 and/or CKDi25 and our bioinformatic follow-up prioritized variants and genes underneath these loci. The OR2S2 locus is novel for any eGFRcrea trait including interesting candidates. For the five genome-wide significant lead variants, we found supporting effects for annual change in blood urea nitrogen or cystatin-based eGFR, but not for GATM or LARP4B. Individuals at high compared to those at low genetic risk (8-14 vs 0-5 adverse alleles) had a 1.20-fold increased risk of acute kidney injury (95% confidence interval 1.08-1.33). Thus, our identified loci for rapid kidney function decline may help prioritize therapeutic targets and identify mechanisms and individuals at risk for sustained deterioration of kidney function.

Metabolites Associated with Walking Ability Among the Oldest Old from the CHS All Stars Study. - Marron, Megan M; Wendell, Stacy G; Boudreau, Robert M; Clish, Clary B; Santanasto, Adam J; Tseng, George C; Zmuda, Joseph M; Newman, Anne B (J Gerontol A Biol Sci Med Sci, 2020)
BACKGROUND: Low walking ability is highly prevalent with advancing age and predicts major health outcomes. Metabolomics may help to better characterize differences in walking ability among older adults, providing insight into potentially altered molecular processes underlying age-related decline in functioning. We sought to identify metabolites and metabolic pathways associated with high versus low walking ability among 120 participants ages 79-95 from the CHS All Stars study. METHODS: Using a nested case-control design, 60 randomly selected participants with low walking ability were matched one-to-one on age, gender, race, and fasting time with 60 participants with high walking ability. High versus low walking ability was defined as being in the best versus worst tertiles for both gait speed (≥0.9 vs <0.7 m/s) and the Walking Ability Index (7-9 vs 0-1). Using liquid chromatography-mass spectrometry, 569 metabolites were identified in overnight-fasting plasma. RESULTS: Ninety-six metabolites were associated with walking ability, where 24% were triacylglycerols. Triacylglycerols that were higher among those with high walking ability consisted mostly of polyunsaturated fatty acids, whereas triacylglycerols that were lower among those with high walking ability consisted mostly of saturated or monounsaturated fatty acids. Body composition partly explained associations between some metabolites and walking ability. Proline and arginine metabolism was a top pathway associated with walking ability. CONCLUSION: These results may partly reflect pathways of modifiable risk factors, including excess dietary lipids and lack of physical activity, contributing to obesity and further alterations in metabolic pathways that lead to age-related decline in walking ability in this older adult cohort.
Keywords: Aged; Aged, 80 and over; Case-Control Studies; Female; Geriatric Assessment; Humans; Male; Metabolomics; Risk Factors; Walking; Walking Speed

Mitochondrial DNA copy number can influence mortality and cardiovascular disease via methylation of nuclear DNA CpGs. - Castellani, Christina A; Longchamps, Ryan J; Sumpter, Jason A; Newcomb, Charles E; Lane, John A; Grove, Megan L; Bressler, Jan; Brody, Jennifer A; Floyd, James S; Bartz, Traci M; Taylor, Kent D; Wang, Penglong; et al. (Genome Med, 2020)
BACKGROUND: Mitochondrial DNA copy number (mtDNA-CN) has been associated with a variety of aging-related diseases, including all-cause mortality. However, the mechanism by which mtDNA-CN influences disease is not currently understood. One such mechanism may be through regulation of nuclear gene expression via the modification of nuclear DNA (nDNA) methylation. METHODS: To investigate this hypothesis, we assessed the relationship between mtDNA-CN and nDNA methylation in 2507 African American (AA) and European American (EA) participants from the Atherosclerosis Risk in Communities (ARIC) study. To validate our findings, we assayed an additional 2528 participants from the Cardiovascular Health Study (CHS) (N = 533) and Framingham Heart Study (FHS) (N = 1995). We further assessed the effect of experimental modification of mtDNA-CN through knockout of TFAM, a regulator of mtDNA replication, via CRISPR-Cas9. RESULTS: Thirty-four independent CpGs were associated with mtDNA-CN at genome-wide significance (P < 5 × 10). Meta-analysis across all cohorts identified six mtDNA-CN-associated CpGs at genome-wide significance (P < 5 × 10). Additionally, over half of these CpGs were associated with phenotypes known to be associated with mtDNA-CN, including coronary heart disease, cardiovascular disease, and mortality. Experimental modification of mtDNA-CN demonstrated that modulation of mtDNA-CN results in changes in nDNA methylation and gene expression of specific CpGs and nearby transcripts. Strikingly, the "neuroactive ligand receptor interaction" KEGG pathway was found to be highly overrepresented in the ARIC cohort (P = 5.24 × 10), as well as the TFAM knockout methylation (P = 4.41 × 10) and expression (P = 4.30 × 10) studies. CONCLUSIONS: These results demonstrate that changes in mtDNA-CN influence nDNA methylation at specific loci and result in differential expression of specific genes that may impact human health and disease via altered cell signaling.

Multi-ancestry GWAS of the electrocardiographic PR interval identifies 202 loci underlying cardiac conduction. - Ntalla, Ioanna; Weng, Lu-Chen; Cartwright, James H; Hall, Amelia Weber; Sveinbjornsson, Gardar; Tucker, Nathan R; Choi, Seung Hoan; Chaffin, Mark D; Roselli, Carolina; Barnes, Michael R; Mifsud, Borbala; Warren, Helen R; et al. (Nat Commun, 2020)
The electrocardiographic PR interval reflects atrioventricular conduction, and is associated with conduction abnormalities, pacemaker implantation, atrial fibrillation (AF), and cardiovascular mortality. Here we report a multi-ancestry (N = 293,051) genome-wide association meta-analysis for the PR interval, discovering 202 loci of which 141 have not previously been reported. Variants at identified loci increase the percentage of heritability explained, from 33.5% to 62.6%. We observe enrichment for cardiac muscle developmental/contractile and cytoskeletal genes, highlighting key regulation processes for atrioventricular conduction. Additionally, 8 loci not previously reported harbor genes underlying inherited arrhythmic syndromes and/or cardiomyopathies suggesting a role for these genes in cardiovascular pathology in the general population. We show that polygenic predisposition to PR interval duration is an endophenotype for cardiovascular disease, including distal conduction disease, AF, and atrioventricular pre-excitation. These findings advance our understanding of the polygenic basis of cardiac conduction, and the genetic relationship between PR interval duration and cardiovascular disease.

The Polygenic and Monogenic Basis of Blood Traits and Diseases. - Vuckovic, Dragana; Bao, Erik L; Akbari, Parsa; Lareau, Caleb A; Mousas, Abdou; Jiang, Tao; Chen, Ming-Huei; Raffield, Laura M; Tardaguila, Manuel; Huffman, Jennifer E; Ritchie, Scott C; Megy, Karyn; et al. (Cell, 2020)
Blood cells play essential roles in human health, underpinning physiological processes such as immunity, oxygen transport, and clotting, which when perturbed cause a significant global health burden. Here we integrate data from UK Biobank and a large-scale international collaborative effort, including data for 563,085 European ancestry participants, and discover 5,106 new genetic variants independently associated with 29 blood cell phenotypes covering a range of variation impacting hematopoiesis. We holistically characterize the genetic architecture of hematopoiesis, assess the relevance of the omnigenic model to blood cell phenotypes, delineate relevant hematopoietic cell states influenced by regulatory genetic variants and gene networks, identify novel splice-altering variants mediating the associations, and assess the polygenic prediction potential for blood traits and clinical disorders at the interface of complex and Mendelian genetics. These results show the power of large-scale blood cell trait GWAS to interrogate clinically meaningful variants across a wide allelic spectrum of human variation.

Pre-diabetes, diabetes and predictors of incident angina among older women and men in the Cardiovascular Health Study. - Mathenge, Njambi; Fan, Wenjun; Wong, Nathan D; Hirsch, Calvin; Delaney, Chris Joseph; Amsterdam, Ezra A; Koch, Bruce; Calara, Rico; Gardin, Julius M (Diab Vasc Dis Res, 2020)
Diabetes mellitus and angina pectoris are important conditions in older persons. The utility of pre-diabetes mellitus, diabetes mellitus and other risk factors as predictors of incident angina pectoris among older adults has not been characterized. We examined incident angina pectoris rates by sex and diabetes mellitus status in 4511 adults aged ⩾65 years without coronary heart disease at baseline from the Cardiovascular Health Study. Cox regression examined predictors of incident angina pectoris, including pre-diabetes mellitus or diabetes mellitus adjusted for sociodemographic characteristics and other risk factors, over 12.2 ± 6.9 years of follow-up. Overall, 39.1% of participants had pre-diabetes mellitus, 14.0% had diabetes mellitus and 532 (11.8%) had incident angina pectoris. Incident angina pectoris rates per 1000 person-years in those with neither condition, pre-diabetes mellitus, and diabetes mellitus were 7.9, 9.0 and 12.3 in women and 10.3, 11.2 and 14.5 in men, respectively. Pre-diabetes mellitus and diabetes mellitus were not independently associated with incident AP; however, key predictors of AP were male sex, low-density lipoprotein-cholesterol, triglycerides, systolic blood pressure, antihypertensive medication and difficulty performing at least one instrumental activity of daily living (all  < 0.05 to  < 0.01). In our cohort of older adult participants, while the incidence of AP is greater in those with diabetes mellitus, neither diabetes mellitus nor pre-diabetes mellitus independently predicted incident angina pectoris.
Keywords: Age Factors; Aged; Angina Pectoris; Diabetes Mellitus; Female; Humans; Incidence; Male; Prediabetic State; Prognosis; Prospective Studies; Risk Assessment; Risk Factors; Sex Factors; Time Factors; United States

Role of Rare and Low-Frequency Variants in Gene-Alcohol Interactions on Plasma Lipid Levels. - Wang, Zhe; Chen, Han; Bartz, Traci M; Bielak, Lawrence F; Chasman, Daniel I; Feitosa, Mary F; Franceschini, Nora; Guo, Xiuqing; Lim, Elise; Noordam, Raymond; Richard, Melissa A; Wang, Heming; et al. (Circ Genom Precis Med, 2020)
BACKGROUND: Alcohol intake influences plasma lipid levels, and such effects may be moderated by genetic variants. We aimed to characterize the role of aggregated rare and low-frequency protein-coding variants in gene by alcohol consumption interactions associated with fasting plasma lipid levels. METHODS: In the Cohorts for Heart and Aging Research in Genomic Epidemiology consortium, fasting plasma triglycerides and high- and low-density lipoprotein cholesterol were measured in 34 153 individuals with European ancestry from 5 discovery studies and 32 277 individuals from 6 replication studies. Rare and low-frequency functional protein-coding variants (minor allele frequency, ≤5%) measured by an exome array were aggregated by genes and evaluated by a gene-environment interaction test and a joint test of genetic main and gene-environment interaction effects. Two dichotomous self-reported alcohol consumption variables, current drinker, defined as any recurrent drinking behavior, and regular drinker, defined as the subset of current drinkers who consume at least 2 drinks per week, were considered. RESULTS: We discovered and replicated 21 gene-lipid associations at 13 known lipid loci through the joint test. Eight loci (, , , , , , , and ) remained significant after conditioning on the common index single-nucleotide polymorphism identified by previous genome-wide association studies, suggesting an independent role for rare and low-frequency variants at these loci. One significant gene-alcohol interaction on triglycerides in a novel locus was significantly discovered (=6.65×10 for the interaction test) and replicated at nominal significance level (=0.013) in . CONCLUSIONS: In conclusion, this study applied new gene-based statistical approaches and suggested that rare and low-frequency genetic variants interacted with alcohol consumption on lipid levels.

Sex-Specific Associations of Cardiovascular Risk Factors and Biomarkers With Incident Heart Failure. - Suthahar, Navin; Lau, Emily S; Blaha, Michael J; Paniagua, Samantha M; Larson, Martin G; Psaty, Bruce M; Benjamin, Emelia J; Allison, Matthew A; Bartz, Traci M; Januzzi, James L; Levy, Daniel; Meems, Laura M G; et al. (J Am Coll Cardiol, 2020)
BACKGROUND: Whether cardiovascular (CV) disease risk factors and biomarkers associate differentially with heart failure (HF) risk in men and women is unclear. OBJECTIVES: The purpose of this study was to evaluate sex-specific associations of CV risk factors and biomarkers with incident HF. METHODS: The analysis was performed using data from 4 community-based cohorts with 12.5 years of follow-up. Participants (recruited between 1989 and 2002) were free of HF at baseline. Biomarker measurements included natriuretic peptides, cardiac troponins, plasminogen activator inhibitor-1, D-dimer, fibrinogen, C-reactive protein, sST2, galectin-3, cystatin-C, and urinary albumin-to-creatinine ratio. RESULTS: Among 22,756 participants (mean age 60 ± 13 years, 53% women), HF occurred in 2,095 participants (47% women). Age, smoking, type 2 diabetes mellitus, hypertension, body mass index, atrial fibrillation, myocardial infarction, left ventricular hypertrophy, and left bundle branch block were strongly associated with HF in both sexes (p < 0.001), and the combined clinical model had good discrimination in men (C-statistic = 0.80) and in women (C-statistic = 0.83). The majority of biomarkers were strongly and similarly associated with HF in both sexes. The clinical model improved modestly after adding natriuretic peptides in men (ΔC-statistic = 0.006; likelihood ratio chi-square = 146; p < 0.001), and after adding cardiac troponins in women (ΔC-statistic = 0.003; likelihood ratio chi-square = 73; p < 0.001). CONCLUSIONS: CV risk factors are strongly and similarly associated with incident HF in both sexes, highlighting the similar importance of risk factor control in reducing HF risk in the community. There are subtle sex-related differences in the predictive value of individual biomarkers, but the overall improvement in HF risk estimation when included in a clinical HF risk prediction model is limited in both sexes.

A systematic review and participant-level meta-analysis found little association of retinal microvascular caliber and reduced kidney function. - Lye, Weng Kit; Paterson, Euan; Patterson, Christopher C; Maxwell, Alexander P; Binte Mohammed Abdul, Riswana Banu; Tai, E Shyong; Cheng, Ching Yu; Kayama, Takamasa; Yamashita, Hidetoshi; Sarnak, Mark; Shlipak, Michael; Matsushita, Kunihiro; et al. (Kidney Int, 2020)
Previously, variation in retinal vascular caliber has been reported in association with chronic kidney disease (CKD) but findings remain inconsistent. To help clarify this we conducted individual participant data meta-analysis and aggregate data meta-analysis on summary estimates to evaluate cross-sectional associations between retinal vascular caliber and CKD. A systematic review was performed using Medline and EMBASE for articles published until October 2018. The aggregate analysis used a two-stage approach combining summary estimates from eleven studies (44,803 patients) while the individual participant analysis used a one-stage approach combining raw data from nine studies (33,222 patients). CKD stages 3-5 was defined as an estimated glomerular filtration rate under 60 mL/min/1.73m. Retinal arteriolar and venular caliber (central retinal arteriolar and venular equivalent) were assessed from retinal photographs using computer-assisted methods. Logistic regression estimated relative risk of CKD stages 3-5 associated with a 20 μm decrease (approximately one standard deviation) in central retinal arteriolar and venular equivalent. Prevalence of CKD stages 3-5 was 11.2 % of 33,222 and 11.3 % of 44,803 patients in the individual participant and aggregate data analysis, respectively. No significant associations were detected in adjusted analyses between central retinal arteriolar and venular equivalent and CKD stages 3-5 in the aggregate analysis for central retinal arteriolar relative risk (0.98, 95% confidence interval 0.94-1.03); venular equivalent (0.99, 0.95- 1.04) or individual participant central retinal arteriolar (0.99, 0.95-1.04) or venular equivalent (1.01, 0.97-1.05). Thus, meta-analysis provided little evidence to suggest that cross sectional direct measurements of retinal vascular caliber was associated with CKD stages 3-5 in the general population. Hence, meta-analyses of longitudinal studies evaluating the association between retinal parameters and CKD stages 3-5 may be warranted.

Trans-ethnic and Ancestry-Specific Blood-Cell Genetics in 746,667 Individuals from 5 Global Populations. - Chen, Ming-Huei; Raffield, Laura M; Mousas, Abdou; Sakaue, Saori; Huffman, Jennifer E; Moscati, Arden; Trivedi, Bhavi; Jiang, Tao; Akbari, Parsa; Vuckovic, Dragana; Bao, Erik L; Zhong, Xue; et al. (Cell, 2020)
Most loci identified by GWASs have been found in populations of European ancestry (EUR). In trans-ethnic meta-analyses for 15 hematological traits in 746,667 participants, including 184,535 non-EUR individuals, we identified 5,552 trait-variant associations at p < 5 × 10, including 71 novel associations not found in EUR populations. We also identified 28 additional novel variants in ancestry-specific, non-EUR meta-analyses, including an IL7 missense variant in South Asians associated with lymphocyte count in vivo and IL-7 secretion levels in vitro. Fine-mapping prioritized variants annotated as functional and generated 95% credible sets that were 30% smaller when using the trans-ethnic as opposed to the EUR-only results. We explored the clinical significance and predictive value of trans-ethnic variants in multiple populations and compared genetic architecture and the effect of natural selection on these blood phenotypes between populations. Altogether, our results for hematological traits highlight the value of a more global representation of populations in genetic studies.

Twenty-seven-year time trends in dementia incidence in Europe and the United States: The Alzheimer Cohorts Consortium - Wolters, Frank J; Chibnik, L B; Waziry, Reem; Anderson, Roy (Neurology, 2020)

Whole Blood DNA Methylation Signatures of Diet Are Associated With Cardiovascular Disease Risk Factors and All-Cause Mortality. - Ma, Jiantao; Rebholz, Casey M; Braun, Kim V E; Reynolds, Lindsay M; Aslibekyan, Stella; Xia, Rui; Biligowda, Niranjan G; Huan, Tianxiao; Liu, Chunyu; Mendelson, Michael M; Joehanes, Roby; Hu, Emily A; et al. (Circ Genom Precis Med, 2020)
BACKGROUND: DNA methylation patterns associated with habitual diet have not been well studied. METHODS: Diet quality was characterized using a Mediterranean-style diet score and the Alternative Healthy Eating Index score. We conducted ethnicity-specific and trans-ethnic epigenome-wide association analyses for diet quality and leukocyte-derived DNA methylation at over 400 000 CpGs (cytosine-guanine dinucleotides) in 5 population-based cohorts including 6662 European ancestry, 2702 African ancestry, and 360 Hispanic ancestry participants. For diet-associated CpGs identified in epigenome-wide analyses, we conducted Mendelian randomization (MR) analysis to examine their relations to cardiovascular disease risk factors and examined their longitudinal associations with all-cause mortality. RESULTS: We identified 30 CpGs associated with either Mediterranean-style diet score or Alternative Healthy Eating Index, or both, in European ancestry participants. Among these CpGs, 12 CpGs were significantly associated with all-cause mortality (Bonferroni corrected <1.6×10). Hypermethylation of cg18181703 () was associated with higher scores of both Mediterranean-style diet score and Alternative Healthy Eating Index and lower risk for all-cause mortality (=5.7×10). Ten additional diet-associated CpGs were nominally associated with all-cause mortality (<0.05). MR analysis revealed 8 putatively causal associations for 6 CpGs with 4 cardiovascular disease risk factors (body mass index, triglycerides, high-density lipoprotein cholesterol concentrations, and type 2 diabetes mellitus; Bonferroni corrected MR <4.5×10). For example, hypermethylation of cg11250194 () was associated with lower triglyceride concentrations (MR, =1.5×10).and hypermethylation of cg02079413 (; ) was associated with body mass index (corrected MR, =1×10). CONCLUSIONS: Habitual diet quality was associated with differential peripheral leukocyte DNA methylation levels of 30 CpGs, most of which were also associated with multiple health outcomes, in European ancestry individuals. These findings demonstrate that integrative genomic analysis of dietary information may reveal molecular targets for disease prevention and treatment.

Whole genome sequence analysis of pulmonary function and COPD in 19,996 multi-ethnic participants. - Zhao, Xutong; Qiao, Dandi; Yang, Chaojie; Kasela, Silva; Kim, Wonji; Ma, Yanlin; Shrine, Nick; Batini, Chiara; Sofer, Tamar; Taliun, Sarah A Gagliano; Sakornsakolpat, Phuwanat; Balte, Pallavi P; et al. (Nat Commun, 2020)
Chronic obstructive pulmonary disease (COPD), diagnosed by reduced lung function, is a leading cause of morbidity and mortality. We performed whole genome sequence (WGS) analysis of lung function and COPD in a multi-ethnic sample of 11,497 participants from population- and family-based studies, and 8499 individuals from COPD-enriched studies in the NHLBI Trans-Omics for Precision Medicine (TOPMed) Program. We identify at genome-wide significance 10 known GWAS loci and 22 distinct, previously unreported loci, including two common variant signals from stratified analysis of African Americans. Four novel common variants within the regions of PIAS1, RGN (two variants) and FTO show evidence of replication in the UK Biobank (European ancestry n ~ 320,000), while colocalization analyses leveraging multi-omic data from GTEx and TOPMed identify potential molecular mechanisms underlying four of the 22 novel loci. Our study demonstrates the value of performing WGS analyses and multi-omic follow-up in cohorts of diverse ancestry.
Keywords: Adult; African Americans; Aged; Aged, 80 and over; Alpha-Ketoglutarate-Dependent Dioxygenase FTO; Calcium-Binding Proteins; Feasibility Studies; Female; Follow-Up Studies; Genetic Loci; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Intracellular Signaling Peptides and Proteins; Lung; Male; Middle Aged; Polymorphism, Single Nucleotide; Protein Inhibitors of Activated STAT; Pulmonary Disease, Chronic Obstructive; Respiratory Physiological Phenomena; Small Ubiquitin-Related Modifier Proteins; Whole Genome Sequencing

{Association between ABO haplotypes and the risk of venous thrombosis: impact on disease risk estimation - Goumidi, L.; Thibord, F.; Wiggins, K. L.; Li-Gao, R.; Brown, M. R.; van Hylckama Vlieg, A.; Souto, J. C.; Soria, J. M.; Ibrahim-Kosta, M.; Saut, N.; Daian, D.; Olaso, R.; et al. (Blood, 2021)
10.1182/blood.2020008997Genetic risk score (GRS) analysis is a popular approach to derive individual risk prediction models for complex diseases. In venous thrombosis (VT), such type of analysis shall integrate information at the ABO blood group locus, which is one of the major susceptibility loci. However, there is no consensus about which single nucleotide polymorphisms (SNPs) must be investigated when properly assessing association between ABO locus and VT risk. Using comprehensive haplotype analyses of ABO blood group tagging SNPs in 5425 cases and 8445 controls from 6 studies, we demonstrate that using only rs8176719 (tagging O1) to correctly assess the impact of ABO locus on VT risk is suboptimal, because 5% of rs8176719-delG carriers do not have an increased risk of developing VT. Instead, we recommend the use of 4 SNPs, rs2519093 (tagging A1), rs1053878 (A2), rs8176743 (B), and rs41302905 (O2), when assessing the impact of ABO locus on VT risk to avoid any risk misestimation. Compared with the O1 haplotype, the A2 haplotype is associated with a modest increase in VT risk (odds ratio, ∼1.2), the A1 and B haplotypes are associated with an ∼1.8-fold increased risk, whereas the O2 haplotype tends to be slightly protective (odds ratio, ∼0.80). In addition, although the A1 and B blood groups are associated with increased von Willebrand factor and factor VIII plasma levels, only the A1 blood group is associated with ICAM levels, but in an opposite direction, leaving additional avenues to be explored to fully understand the spectrum of biological effects mediated by ABO locus on cardiovascular traits.

Association Between Myocardial Strain and Frailty in CHS. - Tan, Annabel X; Shah, Sanjiv J; Sanders, Jason L; Psaty, Bruce M; Wu, Chenkai; Gardin, Julius M; Peralta, Carmen A; Newman, Anne B; Odden, Michelle C (Circ Cardiovasc Imaging, 2021)
BACKGROUND: Myocardial strain, measured by speckle-tracking echocardiography, is a novel measure of subclinical cardiovascular disease and may reflect myocardial aging. We evaluated the association between myocardial strain and frailty-a clinical syndrome of lack of physiological reserve. METHODS: Frailty was defined in participants of the CHS (Cardiovascular Health Study) as having ≥3 of the following clinical criteria: weakness, slowness, weight loss, exhaustion, and inactivity. Using speckle-tracking echocardiography data, we examined the cross-sectional (n=3206) and longitudinal (n=1431) associations with frailty among participants who had at least 1 measure of myocardial strain, left ventricular longitudinal strain (LVLS), left ventricular early diastolic strain rate and left atrial reservoir strain, and no history of cardiovascular disease or heart failure at the time of echocardiography. RESULTS: In cross-sectional analyses, lower (worse) LVLS was associated with prevalent frailty; this association was robust to adjustment for left ventricular ejection fraction (adjusted odds ratio, 1.32 [95% CI, 1.07-1.61] per 1-SD lower strain; =0.007) and left ventricular stroke volume (adjusted OR, 1.32 [95% CI, 1.08-1.61] per 1-SD lower strain; =0.007). In longitudinal analyses, adjusted associations of LVLS and left ventricular early diastolic strain with incident frailty were 1.35 ([95% CI, 0.96-1.89] =0.086) and 1.58 ([95% CI, 1.11-2.27] =0.013, respectively). Participants who were frail and had the worst LVLS had a 2.2-fold increased risk of death (hazard ratio, 2.20 [95% CI, 1.81-2.66]; <0.0001). CONCLUSIONS: In community-dwelling older adults without prevalent cardiovascular disease, worse LVLS by speckle-tracking echocardiography, reflective of subclinical myocardial dysfunction, was associated with frailty. Frailty and LVLS have an additive effect on mortality risk.

Association Between Preserved Ratio Impaired Spirometry and Clinical Outcomes in US Adults. - Wan, Emily S; Balte, Pallavi; Schwartz, Joseph E; Bhatt, Surya P; Cassano, Patricia A; Couper, David; Daviglus, Martha L; Dransfield, Mark T; Gharib, Sina A; Jacobs, David R; Kalhan, Ravi; London, Stephanie J; et al. (JAMA, 2021)
Importance: Chronic lung diseases are a leading cause of morbidity and mortality. Unlike chronic obstructive pulmonary disease, clinical outcomes associated with proportional reductions in expiratory lung volumes without obstruction, otherwise known as preserved ratio impaired spirometry (PRISm), are poorly understood. Objective: To examine the prevalence, correlates, and clinical outcomes associated with PRISm in US adults. Design, Setting, and Participants: The National Heart, Lung, and Blood Institute (NHLBI) Pooled Cohorts Study was a retrospective study with harmonized pooled data from 9 US general population-based cohorts (enrollment, 65 251 participants aged 18 to 102 years of whom 53 701 participants had valid baseline lung function) conducted from 1971-2011 (final follow-up, December 2018). Exposures: Participants were categorized into mutually exclusive groups by baseline lung function. PRISm was defined as the ratio of forced expiratory volume in the first second to forced vital capacity (FEV1:FVC) greater than or equal to 0.70 and FEV1 less than 80% predicted; obstructive spirometry FEV1:FVC ratio of less than 0.70; and normal spirometry FEV1:FVC ratio greater than or equal to 0.7 and FEV1 greater than or equal to 80% predicted. Main Outcomes and Measures: Main outcomes were all-cause mortality, respiratory-related mortality, coronary heart disease (CHD)-related mortality, respiratory-related events (hospitalizations and mortality), and CHD-related events (hospitalizations and mortality) classified by adjudication or validated administrative criteria. Absolute risks were adjusted for age and smoking status. Poisson and Cox proportional hazards models comparing PRISm vs normal spirometry were adjusted for age, sex, race and ethnicity, education, body mass index, smoking status, cohort, and comorbidities. Results: Among all participants (mean [SD] age, 53.2 [15.8] years, 56.4% women, 48.5% never-smokers), 4582 (8.5%) had PRISm. The presence of PRISm relative to normal spirometry was significantly associated with obesity (prevalence, 48.3% vs 31.4%; prevalence ratio [PR], 1.68 [95% CI, 1.55-1.82]), underweight (prevalence, 1.4% vs 1.0%; PR, 2.20 [95% CI, 1.72-2.82]), female sex (prevalence, 60.3% vs 59.0%; PR, 1.07 [95% CI, 1.01-1.13]), and current smoking (prevalence, 25.2% vs 17.5%; PR, 1.33 [95% CI, 1.22-1.45]). PRISm, compared with normal spirometry, was significantly associated with greater all-cause mortality (29.6/1000 person-years vs 18.0/1000 person-years; difference, 11.6/1000 person-years [95% CI, 10.0-13.1]; adjusted hazard ratio [HR], 1.50 [95% CI, 1.42-1.59]), respiratory-related mortality (2.1/1000 person-years vs 1.0/1000 person-years; difference, 1.1/1000 person-years [95% CI, 0.7-1.6]; adjusted HR, 1.95 [95% CI, 1.54-2.48]), CHD-related mortality (5.4/1000 person-years vs 2.6/1000 person-years; difference, 2.7/1000 person-years [95% CI, 2.1-3.4]; adjusted HR, 1.55 [95% CI, 1.36-1.77]), respiratory-related events (12.2/1000 person-years vs 6.0/1000 person-years; difference, 6.2/1000 person-years [95% CI, 4.9-7.5]; adjusted HR, 1.90 [95% CI, 1.69-2.14]), and CHD-related events (11.7/1000 person-years vs 7.0/1000 person-years; difference, 4.7/1000 person-years [95% CI, 3.7-5.8]; adjusted HR, 1.30 [95% CI, 1.18-1.42]). Conclusions and Relevance: In a large, population-based sample of US adults, baseline PRISm, compared with normal spirometry, was associated with a small but statistically significant increased risk for mortality and adverse cardiovascular and respiratory outcomes. Further research is needed to explore whether this association is causal.
Keywords: Adult; Aged; Aged, 80 and over; Cardiovascular Diseases; Female; Forced Expiratory Volume; Humans; Lung; Lung Diseases; Male; Middle Aged; Prevalence; Retrospective Studies; Spirometry; United States; Vital Capacity

Association of low-frequency and rare coding variants with information processing speed. - Bressler, Jan; Davies, Gail; Smith, Albert V; Saba, Yasaman; Bis, Joshua C; Jian, Xueqiu; Hayward, Caroline; Yanek, Lisa; Smith, Jennifer A; Mirza, Saira S; Wang, Ruiqi; Adams, Hieab H H; et al. (Transl Psychiatry, 2021)
Measures of information processing speed vary between individuals and decline with age. Studies of aging twins suggest heritability may be as high as 67%. The Illumina HumanExome Bead Chip genotyping array was used to examine the association of rare coding variants with performance on the Digit-Symbol Substitution Test (DSST) in community-dwelling adults participating in the Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) Consortium. DSST scores were available for 30,576 individuals of European ancestry from nine cohorts and for 5758 individuals of African ancestry from four cohorts who were older than 45 years and free of dementia and clinical stroke. Linear regression models adjusted for age and gender were used for analysis of single genetic variants, and the T5, T1, and T01 burden tests that aggregate the number of rare alleles by gene were also applied. Secondary analyses included further adjustment for education. Meta-analyses to combine cohort-specific results were carried out separately for each ancestry group. Variants in RNF19A reached the threshold for statistical significance (p = 2.01 × 10) using the T01 test in individuals of European descent. RNF19A belongs to the class of E3 ubiquitin ligases that confer substrate specificity when proteins are ubiquitinated and targeted for degradation through the 26S proteasome. Variants in SLC22A7 and OR51A7 were suggestively associated with DSST scores after adjustment for education for African-American participants and in the European cohorts, respectively. Further functional characterization of its substrates will be required to confirm the role of RNF19A in cognitive function.
Keywords: Adult; Aging; Cognition; Genome-Wide Association Study; Geroscience; Humans; Polymorphism, Single Nucleotide; Ubiquitin-Protein Ligases

Association of Midlife Cardiovascular Risk Factors With the Risk of Heart Failure Subtypes Later in Life. - Cohen, Laura P; Vittinghoff, Eric; Pletcher, Mark J; Allen, Norrina B; Shah, Sanjiv J; Wilkins, John T; Chang, Patricia P; Ndumele, Chiadi E; Newman, Anne B; Ives, Diane; Maurer, Mathew S; Oelsner, Elizabeth C; et al. (J Card Fail, 2021)
BACKGROUND: Independent associations between cardiovascular risk factor exposures during midlife and later life development of heart failure (HF) with preserved ejection fraction (HFpEF) versus reduced EF (HFrEF) have not been previously studied. METHODS: We pooled data from 4 US cohort studies (Atherosclerosis Risk in Communities, Cardiovascular Health, Health , Aging and Body Composition, and Multi-Ethnic Study of Atherosclerosis) and imputed annual risk factor trajectories for body mass index, systolic and diastolic blood pressure, low-density lipoprotein and high-density lipoprotein cholesterol, and glucose starting from age 40 years. Time-weighted average exposures to each risk factor during midlife and later life were calculated and analyzed for associations with the development of HFpEF or HFrEF. RESULTS: A total of 23,861 participants were included (mean age at first in-person visit, 61.8 ±1 0.2 years; 56.6% female). During a median follow-up of 12 years, there were 3666 incident HF events, of which 51% had EF measured, including 934 with HFpEF and 739 with HFrEF. A high midlife systolic blood pressure and low midlife high-density lipoprotein cholesterol were associated with HFrEF, and a high midlife body mass index, systolic blood pressure, pulse pressure, and glucose were associated with HFpEF. After adjusting for later life exposures, only midlife pulse pressure remained independently associated with HFpEF. CONCLUSIONS: Midlife exposure to cardiovascular risk factors are differentially associated with HFrEF and HFpEF later in life. Having a higher pulse pressure during midlife is associated with a greater risk for HFpEF but not HFrEF, independent of later life exposures.

Association of mitochondrial DNA copy number with cardiometabolic diseases. - Liu, Xue; Longchamps, Ryan J; Wiggins, Kerri L; Raffield, Laura M; Bielak, Lawrence F; Zhao, Wei; Pitsillides, Achilleas; Blackwell, Thomas W; Yao, Jie; Guo, Xiuqing; Kurniansyah, Nuzulul; Thyagarajan, Bharat; et al. (Cell Genom, 2021)
Mitochondrial DNA (mtDNA) is present in multiple copies in human cells. We evaluated cross-sectional associations of whole blood mtDNA copy number (CN) with several cardiometabolic disease traits in 408,361 participants of multiple ancestries in TOPMed and UK Biobank. Age showed a threshold association with mtDNA CN: among younger participants (<65 years of age), each additional 10 years of age was associated with 0.03 standard deviation (s.d.) higher level of mtDNA CN ( = 0.0014) versus a 0.14 s.d. lower level of mtDNA CN ( = 1.82 × 10) among older participants (≥65 years). At lower mtDNA CN levels, we found age-independent associations with increased odds of obesity ( = 5.6 × 10), hypertension ( = 2.8 × 10), diabetes ( = 3.6 × 10), and hyperlipidemia ( = 6.3 × 10). The observed decline in mtDNA CN after 65 years of age may be a key to understanding age-related diseases.

Association of Retail Environment and Neighborhood Socioeconomic Status with Mortality among Community-dwelling Older Adults in the US: Cardiovascular Health Study. - Zhang, Kehan; Lovasi, Gina S; Odden, Michelle C; Michael, Yvonne L; Newman, Anne B; Arnold, Alice M; Kim, Dae Hyun; Wu, Chenkai (J Gerontol A Biol Sci Med Sci, 2021)
BACKGROUND: Few studies have examined the association of neighborhood environment and mortality among community-dwelling older populations. Geographic Information Systems (GIS)-based measures of neighborhood physical environment may provide new insights on the health effects of the social and built environment. METHODS: We studied 4,379 community-dwelling older adults in the US aged ≥65 years from the Cardiovascular Health Study. Principal component analysis was used to identify neighborhood components from 48 variables assessing facilities and establishments, demographic composition, socio-economic status, and economic prosperity. We used a Cox model to evaluate the association of neighborhood components with five-year mortality. Age, sex, race, education, income, marital status, body mass index, smoking status, disability, coronary heart disease, and diabetes were included as covariates. We also examined the interactions between neighborhood components and sex and race (Black vs. white or other). RESULTS: We identified five neighborhood components, representing facilities and resources, immigrant communities, community-level economic deprivation, resident-level socio-economic status and residents' age. Communities' economic deprivation and residents' socio-economic status were significantly associated with five-year mortality. We did not find interactions between sex or race and any of the five neighborhood components. The results were similar in a sensitivity analysis where we used ten-year mortality as the outcome. CONCLUSIONS: We found that communities' economic status but not facilities in communities was associated with mortality among older adults. These findings revealed the importance and benefits living in a socio-economically advantaged neighborhood could have on health among older residents with different demographic backgrounds.

Association of Trimethylamine N-Oxide and Related Metabolites in Plasma and Incident Type 2 Diabetes: The Cardiovascular Health Study. - Lemaitre, Rozenn N; Jensen, Paul N; Wang, Zeneng; Fretts, Amanda M; McKnight, Barbara; Nemet, Ina; Biggs, Mary L; Sotoodehnia, Nona; de Oliveira Otto, Marcia C; Psaty, Bruce M; Siscovick, David S; Hazen, Stanley L; et al. (JAMA Netw Open, 2021)
Importance: Although rodent studies suggest that trimethylamine N-oxide (TMAO) influences glucose homeostasis and risk of type 2 diabetes, evidence in humans is limited. Objective: To examine the associations of serial measures of plasma TMAO and related metabolite concentrations with incident type 2 diabetes, fasting plasma insulin and glucose levels, and the Gutt insulin sensitivity index (ISI). Design, Setting, and Participants: This prospective cohort design assessed the association of plasma TMAO and related metabolite concentrations with diabetes outcome, whereas a cross-sectional design assessed the association with insulin and glucose levels and Gutt ISI. The participants were a cohort of older US adults from the Cardiovascular Health Study (CHS). Data from June 1989 to May 1990, from November 1992 to June 1993, and from June 1995 to June 1997 were included, with follow-up through June 2010. Levels of TMAO and related metabolites were measured in CHS plasma samples. Data were analyzed from July 2019 to September 2020. Exposures: Plasma concentrations of TMAO, carnitine, betaine, choline, crotonobetaine, and γ-butyrobetaine, measured by high-performance liquid chromatography and mass spectrometry. Main Outcomes and Measures: Linear regression for associations of TMAO and related metabolites with insulin and glucose levels and Gutt ISI, and proportional hazards regression for associations with diabetes. Results: The study included 4442 participants without diabetes at baseline (mean [SD] age, 73 [6] years at entry; 2710 [61%] women). In multivariable analyses, plasma TMAO, carnitine, crotonobetaine, and γ-butyrobetaine concentrations were positively associated with fasting insulin level (insulin mean geometric ratio comparing fifth with first quintiles of metabolite concentration: 1.07 [95% CI, 1.04-1.10] for TMAO; 1.07 [95% CI, 1.03-1.10] for carnitine; 1.05 [95% CI, 1.02-1.08] for crotonobetaine; and 1.06 [95% CI, 1.02-1.09] for γ-butyrobetaine). In contrast, betaine and choline concentrations were associated with greater insulin sensitivity (mean difference in Gutt ISI comparing fifth with first quintiles: 6.46 [95% CI, 4.32-8.60] and 2.27 [95% CI, 0.16-4.38], respectively). Incident diabetes was identified in 661 participants during a median 12.1 (interquartile range, 6.9-17.1) years of follow-up. In multivariable analyses, TMAO and metabolites were not significantly associated with type 2 diabetes risk (hazard ratios of diabetes comparing fifth with first quintile: 1.20 [95% CI, 0.94-1.55] for TMAO; 0.96 [95% CI, 0.74-1.24] for choline; 0.88 [95% CI, 0.67-1.15] for betaine; 1.07 [95% CI, 0.83-1.37] for carnitine; 0.79 [95% CI, 0.60-1.04] for γ-butyrobetaine; and 1.06 [95% CI, 0.83-1.35] for crotonobetaine). Conclusions and Relevance: Plasma TMAO and related metabolites were not significantly associated with type 2 diabetes among older adults. The metabolites TMAO, carnitine, γ-butyrobetaine, and crotonobetaine may be associated with insulin resistance, and betaine and choline may be associated with greater insulin sensitivity, but temporality of the associations was not established.

Associations of Body Mass Index and Waist Circumference in Young Adulthood with Later Life Incident Diabetes. - Nair, Nandini; Vittinghoff, Eric; Pletcher, Mark J; Oelsner, Elizabeth C; Allen, Norrina B; Ndumele, Chiadi E; West, Nancy A; Strotmeyer, Elsa S; Mukamal, Kenneth J; Siscovick, David S; Biggs, Mary L; Laferrère, Blandine; et al. (J Clin Endocrinol Metab, 2021)
CONTEXT: The independent contribution of young adult exposure to overweight and obesity to later-life incident diabetes is not well studied. OBJECTIVE: To assess the associations of exposures to elevated body mass index (BMI) and waist circumference (WC) in young adulthood (ages 18-39 years) with incident diabetes later in life (≥40 years). DESIGN: Pooled data from 6 US prospective cohorts (Atherosclerosis Risk in Communities Study, Cardiovascular Risk Development in Young Adults Study, Cardiovascular Health Study, (4) Framingham Heart Study Offspring Cohort, (5) Health, Aging and Body Composition Study, and (6) Multi-Ethnic Study of Atherosclerosis. SETTING: Population-based cohort studies. PARTICIPANTS: 30 780 participants (56.1% female, 69.8% non-Hispanic white) without a diagnosis of diabetes by age 40. INTERVENTIONS: We imputed BMI and WC trajectories from age 18 for every participant and estimated time-weighted average exposures to BMI or WC during young adulthood and later life. MAIN OUTCOME MEASURE(S): Incident diabetes defined as fasting glucose ≥126 mg/dL, nonfasting glucose ≥200 mg/dL, or use of diabetes medications. RESULTS: During a 9-year median follow-up, 4323 participants developed incident diabetes. Young adult BMI and WC were associated with later-life incident diabetes after controlling for later-life exposures [hazard ratios (HR) 1.99 for BMI ≥ 30 kg/m2 and 2.13 for WC > 88cm (women)/>102cm (men) compared to normal ranges]. Young adult homeostatic model of insulin resistance mediated 49% and 44% of the association between BMI and WC with later-life incident diabetes. High-density lipoproteins and triglycerides mediated a smaller proportion of these associations. CONCLUSIONS: Elevated BMI and WC during young adulthood were independently associated with later-life incident diabetes. Insulin resistance may be a key mediator.
Keywords: Adolescent; Adult; Biomarkers; Body Mass Index; Diabetes Mellitus; Female; Follow-Up Studies; Humans; Male; Obesity; Overweight; Prognosis; Prospective Studies; Risk Factors; United States; Waist Circumference; Young Adult

Associations of hemoglobin and change in hemoglobin with risk of incident hip fracture in older men and women: the cardiovascular health study. - Valderrábano, R J; Bůžková, P; Chang, P-Y; Zakai, N A; Fink, H A; Robbins, J A; Wu, J Y; Lee, J S (Osteoporos Int, 2021)
In a multi-site longitudinal cohort study, decreasing hemoglobin was associated with increased hip fracture risk in men. Anemia was associated with hip fracture in men and in African American women. Decreasing hemoglobin may be a marker of progressing bone fragility, making its serial measurement useful for fracture risk stratification. INTRODUCTION: Hematopoiesis and bone health are interdependent. Anemia has been associated with risk of fracture in humans. To further elucidate this relationship, we hypothesized that decreasing hemoglobin could indicate defective hematopoiesis and would also predict fracture risk. METHODS: We performed a prospective analysis from study baseline (1992) of the Cardiovascular Health Study, a multi-site longitudinal cohort study. A total of 4670 men and women, ages >65 years, who were able to consent and not institutionalized or wheelchair bound, had hemoglobin (Hb) measured in 1992. For 4006 subjects, Hb change from 1989 to 1992 was annualized and divided into sex-specific quartiles. Incident hip fractures were verified against Medicare claims data during a median follow-up of 11.8 years. RESULTS: Nested Cox proportional-hazard models estimated association of hip fracture with anemia (men Hb <13 g/dL, women Hb <12 g/dL) and separately, greatest Hb decrease (versus others). Anemia was associated with increased hip fracture risk in all men (HR 1.59; 95% CI 1.01-2.50) and African American women (HR 3.21; 95% CI 1.07-9.63). In men, an annualized Hb loss of >0.36 g/dL/year was associated with a higher risk of hip fracture (HR 1.67; 95% CI 1.10-2.54), which was lessened by anemia at the start of fracture follow-up (HR 1.53; 95% CI 0.99-2.39). CONCLUSIONS: Decreasing Hb may be an early marker for subsequent hip fracture risk in men, which may be less informative once an anemia threshold is crossed. Only African American women with anemia had increased hip fracture risk, suggesting a race difference in this relationship.

Blood n-3 fatty acid levels and total and cause-specific mortality from 17 prospective studies. - Harris, William S; Tintle, Nathan L; Imamura, Fumiaki; Qian, Frank; Korat, Andres V Ardisson; Marklund, Matti; Djoussé, Luc; Bassett, Julie K; Carmichael, Pierre-Hugues; Chen, Yun-Yu; Hirakawa, Yoichiro; Küpers, Leanne K; et al. (Nat Commun, 2021)
The health effects of omega-3 fatty acids have been controversial. Here we report the results of a de novo pooled analysis conducted with data from 17 prospective cohort studies examining the associations between blood omega-3 fatty acid levels and risk for all-cause mortality. Over a median of 16 years of follow-up, 15,720 deaths occurred among 42,466 individuals. We found that, after multivariable adjustment for relevant risk factors, risk for death from all causes was significantly lower (by 15-18%, at least p < 0.003) in the highest vs the lowest quintile for circulating long chain (20-22 carbon) omega-3 fatty acids (eicosapentaenoic, docosapentaenoic, and docosahexaenoic acids). Similar relationships were seen for death from cardiovascular disease, cancer and other causes. No associations were seen with the 18-carbon omega-3, alpha-linolenic acid. These findings suggest that higher circulating levels of marine n-3 PUFA are associated with a lower risk of premature death.
Keywords: Aged; Aged, 80 and over; Cause of Death; Fatty Acids, Omega-3; Female; Follow-Up Studies; Humans; Male; Middle Aged; Mortality, Premature; Prospective Studies; Protective Factors; Risk Factors

Cardiovascular damage phenotypes and all-cause and CVD mortality in older adults. - Miller, Lindsay M; Wu, Chenkai; Hirsch, Calvin H; Lopez, Oscar L; Cushman, Mary; Odden, Michelle C (Ann Epidemiol, 2021)
PURPOSE: The association between CVD risk factors and mortality is well established, however, current tools for addressing subgroups have focused on the overall burden of disease. The identification of risky combinations of characteristics may lead to a better understanding of physiologic pathways that underlie morbidity and mortality in older adults. METHODS: Participants included 5067 older adults from the Cardiovascular Health Study, followed for up to 6 years. Using latent class analysis (LCA), we created CV damage phenotypes based on probabilities of abnormal brain infarctions, major echocardiogram abnormalities, N-terminal probrain natriuretic peptide, troponin T, interleukin-6, c reactive-protein, galectin-3, cystatin C. We assigned class descriptions based on the probability of having an abnormality among risk factors, such that a healthy phenotype would have low probabilities in all risk factors. Participants were assigned to phenotypes based on the maximum probability of membership. We used Cox-proportional hazards regression to evaluate the association between the categorical CV damage phenotype and all-cause and CVD-mortality. RESULTS: The analysis yielded 5 CV damage phenotypes consistent with the following descriptions: healthy (59%), cardio-renal (11%), cardiac (15%), multisystem morbidity (6%), and inflammatory (9%). All four phenotypes were statistically associated with a greater risk of all-cause mortality when compared with the healthy phenotype. The multisystem morbidity phenotype had the greatest risk of all-cause death (HR: 4.02; 95% CI: 3.44, 4.70), and CVD-mortality (HR: 4.90, 95% CI: 3.95, 6.06). CONCLUSIONS: Five CV damage phenotypes emerged from CVD risk factor measures. CV damage across multiple systems confers a greater mortality risk compared to damage in any single domain.

Chromosome Xq23 is associated with lower atherogenic lipid concentrations and favorable cardiometabolic indices. - Natarajan, Pradeep; Pampana, Akhil; Graham, Sarah E; Ruotsalainen, Sanni E; Perry, James A; de Vries, Paul S; Broome, Jai G; Pirruccello, James P; Honigberg, Michael C; Aragam, Krishna; Wolford, Brooke; Brody, Jennifer A; et al. (Nat Commun, 2021)
Autosomal genetic analyses of blood lipids have yielded key insights for coronary heart disease (CHD). However, X chromosome genetic variation is understudied for blood lipids in large sample sizes. We now analyze genetic and blood lipid data in a high-coverage whole X chromosome sequencing study of 65,322 multi-ancestry participants and perform replication among 456,893 European participants. Common alleles on chromosome Xq23 are strongly associated with reduced total cholesterol, LDL cholesterol, and triglycerides (min P = 8.5 × 10), with similar effects for males and females. Chromosome Xq23 lipid-lowering alleles are associated with reduced odds for CHD among 42,545 cases and 591,247 controls (P = 1.7 × 10), and reduced odds for diabetes mellitus type 2 among 54,095 cases and 573,885 controls (P = 1.4 × 10). Although we observe an association with increased BMI, waist-to-hip ratio adjusted for BMI is reduced, bioimpedance analyses indicate increased gluteofemoral fat, and abdominal MRI analyses indicate reduced visceral adiposity. Co-localization analyses strongly correlate increased CHRDL1 gene expression, particularly in adipose tissue, with reduced concentrations of blood lipids.

Determinants of penetrance and variable expressivity in monogenic metabolic conditions across 77,184 exomes. - Goodrich, Julia K; Singer-Berk, Moriel; Son, Rachel; Sveden, Abigail; Wood, Jordan; England, Eleina; Cole, Joanne B; Weisburd, Ben; Watts, Nick; Caulkins, Lizz; Dornbos, Peter; Koesterer, Ryan; et al. (Nat Commun, 2021)
Hundreds of thousands of genetic variants have been reported to cause severe monogenic diseases, but the probability that a variant carrier develops the disease (termed penetrance) is unknown for virtually all of them. Additionally, the clinical utility of common polygenetic variation remains uncertain. Using exome sequencing from 77,184 adult individuals (38,618 multi-ancestral individuals from a type 2 diabetes case-control study and 38,566 participants from the UK Biobank, for whom genotype array data were also available), we apply clinical standard-of-care gene variant curation for eight monogenic metabolic conditions. Rare variants causing monogenic diabetes and dyslipidemias display effect sizes significantly larger than the top 1% of the corresponding polygenic scores. Nevertheless, penetrance estimates for monogenic variant carriers average 60% or lower for most conditions. We assess epidemiologic and genetic factors contributing to risk prediction in monogenic variant carriers, demonstrating that inclusion of polygenic variation significantly improves biomarker estimation for two monogenic dyslipidemias.
Keywords: Adult; Biological Variation, Population; Biomarkers; Diabetes Mellitus, Type 2; Dyslipidemias; Exome; Genetic Predisposition to Disease; Genotype; Humans; Multifactorial Inheritance; Penetrance; Risk Assessment

Discovery and fine-mapping of height loci via high-density imputation of GWASs in individuals of African ancestry. - Graff, Mariaelisa; Justice, Anne E; Young, Kristin L; Marouli, Eirini; Zhang, Xinruo; Fine, Rebecca S; Lim, Elise; Buchanan, Victoria; Rand, Kristin; Feitosa, Mary F; Wojczynski, Mary K; Yanek, Lisa R; et al. (Am J Hum Genet, 2021)
Although many loci have been associated with height in European ancestry populations, very few have been identified in African ancestry individuals. Furthermore, many of the known loci have yet to be generalized to and fine-mapped within a large-scale African ancestry sample. We performed sex-combined and sex-stratified meta-analyses in up to 52,764 individuals with height and genome-wide genotyping data from the African Ancestry Anthropometry Genetics Consortium (AAAGC). We additionally combined our African ancestry meta-analysis results with published European genome-wide association study (GWAS) data. In the African ancestry analyses, we identified three novel loci (SLC4A3, NCOA2, ECD/FAM149B1) in sex-combined results and two loci (CRB1, KLF6) in women only. In the African plus European sex-combined GWAS, we identified an additional three novel loci (RCCD1, G6PC3, CEP95) which were equally driven by AAAGC and European results. Among 39 genome-wide significant signals at known loci, conditioning index SNPs from European studies identified 20 secondary signals. Two of the 20 new secondary signals and none of the 8 novel loci had minor allele frequencies (MAF) < 5%. Of 802 known European height signals, 643 displayed directionally consistent associations with height, of which 205 were nominally significant (p < 0.05) in the African ancestry sex-combined sample. Furthermore, 148 of 241 loci contained ≤20 variants in the credible sets that jointly account for 99% of the posterior probability of driving the associations. In summary, trans-ethnic meta-analyses revealed novel signals and further improved fine-mapping of putative causal variants in loci shared between African and European ancestry populations.

Epigenetic Age and the Risk of Incident Atrial Fibrillation. - Roberts, Jason D; Vittinghoff, Eric; Lu, Ake T; Alonso, Alvaro; Wang, Biqi; Sitlani, Colleen M; Mohammadi-Shemirani, Pedrum; Fornage, Myriam; Kornej, Jelena; Brody, Jennifer A; Arking, Dan E; Lin, Honghuang; et al. (Circulation, 2021)
BACKGROUND: The most prominent risk factor for atrial fibrillation (AF) is chronological age; however, underlying mechanisms are unexplained. Algorithms using epigenetic modifications to the human genome effectively predict chronological age. Chronological and epigenetic predicted ages may diverge in a phenomenon referred to as epigenetic age acceleration (EAA), which may reflect accelerated biological aging. We sought to evaluate for associations between epigenetic age measures and incident AF. METHODS: Measures for 4 epigenetic clocks (Horvath, Hannum, DNA methylation [DNAm] PhenoAge, and DNAm GrimAge) and an epigenetic predictor of PAI-1 (plasminogen activator inhibitor-1) levels (ie, DNAm PAI-1) were determined for study participants from 3 population-based cohort studies. Cox models evaluated for associations with incident AF and results were combined via random-effects meta-analyses. Two-sample summary-level Mendelian randomization analyses evaluated for associations between genetic instruments of the EAA measures and AF. RESULTS: Among 5600 participants (mean age, 65.5 years; female, 60.1%; Black, 50.7%), there were 905 incident AF cases during a mean follow-up of 12.9 years. Unadjusted analyses revealed all 4 epigenetic clocks and the DNAm PAI-1 predictor were associated with statistically significant higher hazards of incident AF, though the magnitudes of their point estimates were smaller relative to the associations observed for chronological age. The pooled EAA estimates for each epigenetic measure, with the exception of Horvath EAA, were associated with incident AF in models adjusted for chronological age, race, sex, and smoking variables. After multivariable adjustment for additional known AF risk factors that could also potentially function as mediators, pooled EAA measures for 2 clocks remained statistically significant. Five-year increases in EAA measures for DNAm GrimAge and DNAm PhenoAge were associated with 19% (adjusted hazard ratio [HR], 1.19 [95% CI, 1.09-1.31]; <0.01) and 15% (adjusted HR, 1.15 [95% CI, 1.05-1.25]; <0.01) higher hazards of incident AF, respectively. Mendelian randomization analyses for the 5 EAA measures did not reveal statistically significant associations with AF. CONCLUSIONS: Our study identified adjusted associations between EAA measures and incident AF, suggesting that biological aging plays an important role independent of chronological age, though a potential underlying causal relationship remains unclear. These aging processes may be modifiable and not constrained by the immutable factor of time.
Keywords: Aged; Aging; Atrial Fibrillation; DNA Methylation; Epigenesis, Genetic; Epigenomics; Female; Follow-Up Studies; Humans; Incidence; Male; Mendelian Randomization Analysis; Middle Aged; Models, Cardiovascular; Models, Genetic

{Epigenome-wide association meta-analysis of DNA methylation with coffee and tea consumption - Karabegović, I.; Portilla-Fernandez, E.; Li, Y.; Ma, J.; Maas, S. C. E.; Sun, D.; Hu, E. A.; Kühnel, B.; Zhang, Y.; Ambatipudi, S.; Fiorito, G.; Huang, J.; et al. (Nat Commun, 2021)
10.1038/s41467-021-22752-6Coffee and tea are extensively consumed beverages worldwide which have received considerable attention regarding health. Intake of these beverages is consistently linked to, among others, reduced risk of diabetes and liver diseases; however, the mechanisms of action remain elusive. Epigenetics is suggested as a mechanism mediating the effects of dietary and lifestyle factors on disease onset. Here we report the results from epigenome-wide association studies (EWAS) on coffee and tea consumption in 15,789 participants of European and African-American ancestries from 15 cohorts. EWAS meta-analysis of coffee consumption reveals 11 CpGs surpassing the epigenome-wide significance threshold (P-value <1.1×10-7), which annotated to the AHRR, F2RL3, FLJ43663, HDAC4, GFI1 and PHGDH genes. Among them, cg14476101 is significantly associated with expression of the PHGDH and risk of fatty liver disease. Knockdown of PHGDH expression in liver cells shows a correlation with expression levels of genes associated with circulating lipids, suggesting a role of PHGDH in hepatic-lipid metabolism. EWAS meta-analysis on tea consumption reveals no significant association, only two CpGs annotated to CACNA1A and PRDM16 genes show suggestive association (P-value <5.0×10-6). These findings indicate that coffee-associated changes in DNA methylation levels may explain the mechanism of action of coffee consumption in conferring risk of diseases.

Epigenome-wide association study of serum urate reveals insights into urate co-regulation and the SLC2A9 locus. - Tin, Adrienne; Schlosser, Pascal; Matias-Garcia, Pamela R; Thio, Chris H L; Joehanes, Roby; Liu, Hongbo; Yu, Zhi; Weihs, Antoine; Hoppmann, Anselm; Grundner-Culemann, Franziska; Min, Josine L; Kuhns, Victoria L Halperin; et al. (Nat Commun, 2021)
Elevated serum urate levels, a complex trait and major risk factor for incident gout, are correlated with cardiometabolic traits via incompletely understood mechanisms. DNA methylation in whole blood captures genetic and environmental influences and is assessed in transethnic meta-analysis of epigenome-wide association studies (EWAS) of serum urate (discovery, n = 12,474, replication, n = 5522). The 100 replicated, epigenome-wide significant (p < 1.1E-7) CpGs explain 11.6% of the serum urate variance. At SLC2A9, the serum urate locus with the largest effect in genome-wide association studies (GWAS), five CpGs are associated with SLC2A9 gene expression. Four CpGs at SLC2A9 have significant causal effects on serum urate levels and/or gout, and two of these partly mediate the effects of urate-associated GWAS variants. In other genes, including SLC7A11 and PHGDH, 17 urate-associated CpGs are associated with conditions defining metabolic syndrome, suggesting that these CpGs may represent a blood DNA methylation signature of cardiometabolic risk factors. This study demonstrates that EWAS can provide new insights into GWAS loci and the correlation of serum urate with other complex traits.
Keywords: Amino Acid Transport System y+; Cohort Studies; CpG Islands; DNA Methylation; Epigenome; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Glucose Transport Proteins, Facilitative; Gout; Humans; Male; Uric Acid

Estimating Systolic Blood Pressure Intervention Trial Participant Posttrial Survival Using Pooled Epidemiologic Cohort Data. - Bellows, Brandon K; Zhang, Yiyi; Zhang, Zugui; Lloyd-Jones, Donald M; Bress, Adam P; King, Jordan B; Kolm, Paul; Cushman, William C; Johnson, Karen C; Tamariz, Leonardo; Oelsner, Elizabeth C; Shea, Steven; et al. (J Am Heart Assoc, 2021)
Background Intensive systolic blood pressure treatment (<120 mm Hg) in SPRINT (Systolic Blood Pressure Intervention Trial) improved survival compared with standard treatment (<140 mm Hg) over a median follow-up of 3.3 years. We projected life expectancy after observed follow-up in SPRINT using SPRINT-eligible participants in the NHLBI-PCS (National Heart, Lung, and Blood Institute Pooled Cohorts Study). Methods and Results We used propensity scores to weight SPRINT-eligible NHLBI-PCS participants to resemble SPRINT participants. In SPRINT participants, we estimated in-trial survival (<4 years) using a time-based flexible parametric survival model. In SPRINT-eligible NHLBI-PCS participants, we estimated posttrial survival (≥4 years) using an age-based flexible parametric survival model and applied the formula to SPRINT participants to predict posttrial survival. We projected overall life expectancy for each SPRINT participant and compared it to parametric regression (eg, Gompertz) projections based on SPRINT data alone. We included 8584 SPRINT and 10 593 SPRINT-eligible NHLBI-PCS participants. After propensity weighting, mean (SD) age was 67.9 (9.4) and 68.2 (8.8) years, and 35.5% and 37.6% were women in SPRINT and NHLBI-PCS, respectively. Using the NHLBI-PCS-based method, projected mean life expectancy from randomization was 21.0 (7.4) years with intensive and 19.1 (7.2) years with standard treatment. Using the Gompertz regression, life expectancy was 11.2 (2.3) years with intensive and 10.5 (2.2) years with standard treatment. Conclusions Combining SPRINT and NHLBI-PCS observed data likely offers a more realistic estimate of life expectancy than parametrically extrapolating SPRINT data alone. These results offer insight into the potential long-term effectiveness of intensive SBP goals.

FGL1 as a modulator of plasma D-dimer levels: Exome-wide marker analysis of plasma tPA, PAI-1, and D-dimer. - Thibord, Florian; Song, Ci; Pattee, Jack; Rodriguez, Benjamin A T; Chen, Ming-Huei; O'Donnell, Christopher J; Kleber, Marcus E; Delgado, Graciela E; Guo, Xiuqing; Yao, Jie; Taylor, Kent D; Ozel, Ayse Bilge; et al. (J Thromb Haemost, 2021)
BACKGROUND: Use of targeted exome-arrays with common, rare variants and functionally enriched variation has led to discovery of new genes contributing to population variation in risk factors. Plasminogen activator-inhibitor 1 (PAI-1), tissue plasminogen activator (tPA), and the plasma product D-dimer are important components of the fibrinolytic system. There have been few large-scale genome-wide or exome-wide studies of PAI-1, tPA, and D-dimer. OBJECTIVES: We sought to discover new genetic loci contributing to variation in these traits using an exome-array approach. METHODS: Cohort-level analyses and fixed effects meta-analyses of PAI-1 (n = 15 603), tPA (n = 6876,) and D-dimer (n = 19 306) from 12 cohorts of European ancestry with diverse study design were conducted, including single-variant analyses and gene-based burden testing. RESULTS: Five variants located in NME7, FGL1, and the fibrinogen locus, all associated with D-dimer levels, achieved genome-wide significance (P < 5 × 10 ). Replication was sought for these 5 variants, as well as 45 well-imputed variants with P < 1 × 10 in the discovery using an independent cohort. Replication was observed for three out of the five significant associations, including a novel and uncommon (0.013 allele frequency) coding variant p.Trp256Leu in FGL1 (fibrinogen-like-1) with increased plasma D-dimer levels. Additionally, a candidate-gene approach revealed a suggestive association for a coding variant (rs143202684-C) in SERPINB2, and suggestive associations with consistent effect in the replication analysis include an intronic variant (rs11057830-A) in SCARB1 associated with increased D-dimer levels. CONCLUSION: This work provides new evidence for a role of FGL1 in hemostasis.

Genetic insights into biological mechanisms governing human ovarian ageing. - Ruth, Katherine S; Day, Felix R; Hussain, Jazib; Martínez-Marchal, Ana; Aiken, Catherine E; Azad, Ajuna; Thompson, Deborah J; Knoblochova, Lucie; Abe, Hironori; Tarry-Adkins, Jane L; Gonzalez, Javier Martin; Fontanillas, Pierre; et al. (Nature, 2021)
Reproductive longevity is essential for fertility and influences healthy ageing in women, but insights into its underlying biological mechanisms and treatments to preserve it are limited. Here we identify 290 genetic determinants of ovarian ageing, assessed using normal variation in age at natural menopause (ANM) in about 200,000 women of European ancestry. These common alleles were associated with clinical extremes of ANM; women in the top 1% of genetic susceptibility have an equivalent risk of premature ovarian insufficiency to those carrying monogenic FMR1 premutations. The identified loci implicate a broad range of DNA damage response (DDR) processes and include loss-of-function variants in key DDR-associated genes. Integration with experimental models demonstrates that these DDR processes act across the life-course to shape the ovarian reserve and its rate of depletion. Furthermore, we demonstrate that experimental manipulation of DDR pathways highlighted by human genetics increases fertility and extends reproductive life in mice. Causal inference analyses using the identified genetic variants indicate that extending reproductive life in women improves bone health and reduces risk of type 2 diabetes, but increases the risk of hormone-sensitive cancers. These findings provide insight into the mechanisms that govern ovarian ageing, when they act, and how they might be targeted by therapeutic approaches to extend fertility and prevent disease.

{Genome-Wide Association Study of Circulating Interleukin 6 Levels Identifies Novel Loci - Ahluwalia, T. S.; Prins, B. P.; Abdollahi, M.; Armstrong, N. J.; Aslibekyan, S.; Bain, L.; Jefferis, B.; Baumert, J.; Beekman, M.; Ben-Shlomo, Y.; Bis, J. C.; Mitchell, B. D.; et al. (Hum Mol Genet, 2021)
Interleukin-6 (IL-6) is a multifunctional cytokine with both pro- and anti-inflammatory properties with a heritability estimate of up to 61%. The circulating levels of IL-6 in blood have been associated with an increased risk of complex disease pathogenesis. We conducted a two-staged, discovery, and replication meta genome-wide association study (GWAS) of circulating serum IL-6 levels comprising up to 67 428 (ndiscovery = 52 654 and nreplication = 14 774) individuals of European ancestry. The inverse variance fixed-effects based discovery meta-analysis, followed by replication led to the identification of two independent loci, IL1F10/IL1RN rs6734238 on Chromosome (Chr) 2q14, (pcombined = 1.8 × 10-11), HLA-DRB1/DRB5 rs660895 on Chr6p21 (pcombined = 1.5 × 10-10) in the combined meta-analyses of all samples. We also replicated the IL6R rs4537545 locus on Chr1q21 (pcombined = 1.2 × 10-122). Our study identifies novel loci for circulating IL-6 levels uncovering new immunological and inflammatory pathways that may influence IL-6 pathobiology.

{Genome-wide meta-analysis of muscle weakness identifies 15 susceptibility loci in older men and women - Jones, G.; Trajanoska, K.; Santanasto, A. J.; Stringa, N.; Kuo, C. L.; Atkins, J. L.; Lewis, J. R.; Duong, T.; Hong, S.; Biggs, M. L.; Luan, J.; Sarnowski, C.; et al. (Nat Commun, 2021)
Low muscle strength is an important heritable indicator of poor health linked to morbidity and mortality in older people. In a genome-wide association study meta-analysis of 256,523 Europeans aged 60 years and over from 22 cohorts we identify 15 loci associated with muscle weakness (European Working Group on Sarcopenia in Older People definition: n = 48,596 cases, 18.9% of total), including 12 loci not implicated in previous analyses of continuous measures of grip strength. Loci include genes reportedly involved in autoimmune disease (HLA-DQA1 p = 4 × 10-17), arthritis (GDF5 p = 4 × 10-13), cell cycle control and cancer protection, regulation of transcription, and others involved in the development and maintenance of the musculoskeletal system. Using Mendelian randomization we report possible overlapping causal pathways, including diabetes susceptibility, haematological parameters, and the immune system. We conclude that muscle weakness in older adults has distinct mechanisms from continuous strength, including several pathways considered to be hallmarks of ageing.

{The genomics of heart failure: design and rationale of the HERMES consortium - Lumbers, R. T.; Shah, S.; Lin, H.; Czuba, T.; Henry, A.; Swerdlow, D. I.; Malarstig, A.; Andersson, C.; Verweij, N.; Holmes, M. V.; Ärnlöv, J.; Svensson, P.; et al. (ESC Heart Fail, 2021)
The HERMES (HEart failure Molecular Epidemiology for Therapeutic targetS) consortium aims to identify the genomic and molecular basis of heart failure.\ under an additive genetic model.\ HERMES is a global collaboration aiming to (i) identify the genetic determinants of heart failure; (ii) generate insights into the causal pathways leading to heart failure and enable genetic approaches to target prioritization; and (iii) develop genomic tools for disease stratification and risk prediction.

Identification of Functional Genetic Determinants of Cardiac Troponin T and I in a Multiethnic Population and Causal Associations With Atrial Fibrillation. - Yang, Yunju; Bartz, Traci M; Brown, Michael R; Guo, Xiuqing; Zilhão, Nuno R; Trompet, Stella; Weiss, Stefan; Yao, Jie; Brody, Jennifer A; deFilippi, Christopher R; Hoogeveen, Ron C; Lin, Henry J; et al. (Circ Genom Precis Med, 2021)
BACKGROUND: Elevated cardiac troponin levels in blood are associated with increased risk of cardiovascular diseases and mortality. Cardiac troponin levels are heritable, but their genetic architecture remains elusive. METHODS: We conducted a transethnic genome-wide association analysis on high-sensitivity cTnT (cardiac troponin T; hs-cTnT) and high-sensitivity cTnI (cardiac troponin I; hs-cTnI) levels in 24 617 and 14 336 participants free of coronary heart disease and heart failure from 6 population-based cohorts, followed by a series of bioinformatic analyses to decipher the genetic architecture of hs-cTnT and hs-cTnI. RESULTS: We identified 4 genome-wide significant loci for hs-cTnT including a novel locus rs3737882 in and 3 previously reported loci at , , and . One known locus at was replicated for hs-cTnI. One copy of C allele for rs3737882 was associated with a 6% increase in hs-cTnT levels (minor allele frequency, 0.18; =2.80×10). We observed pleiotropic loci located at and . The proportions of variances explained by single-nucleotide polymorphisms were 10.15% and 7.74% for hs-cTnT and hs-cTnI, respectively. Single-nucleotide polymorphisms were colocalized with expression in heart tissues and hs-cTnT and with expression in artery, heart tissues, and whole blood and both troponins. Mendelian randomization analyses showed that genetically increased hs-cTnT and hs-cTnI levels were associated with higher odds of atrial fibrillation (odds ratio, 1.38 [95% CI, 1.25-1.54] for hs-cTnT and 1.21 [95% CI, 1.06-1.37] for hs-cTnI). CONCLUSIONS: We identified a novel genetic locus associated with hs-cTnT in a multiethnic population and found that genetically regulated troponin levels were associated with atrial fibrillation.

Identification of novel and rare variants associated with handgrip strength using whole genome sequence data from the NHLBI Trans-Omics in Precision Medicine (TOPMed) Program. - Sarnowski, Chloe; Chen, Han; Biggs, Mary L; Wassertheil-Smoller, Sylvia; Bressler, Jan; Irvin, Marguerite R; Ryan, Kathleen A; Karasik, David; Arnett, Donna K; Cupples, L Adrienne; Fardo, David W; Gogarten, Stephanie M; et al. (PLoS One, 2021)
Handgrip strength is a widely used measure of muscle strength and a predictor of a range of morbidities including cardiovascular diseases and all-cause mortality. Previous genome-wide association studies of handgrip strength have focused on common variants primarily in persons of European descent. We aimed to identify rare and ancestry-specific genetic variants associated with handgrip strength by conducting whole-genome sequence association analyses using 13,552 participants from six studies representing diverse population groups from the Trans-Omics in Precision Medicine (TOPMed) Program. By leveraging multiple handgrip strength measures performed in study participants over time, we increased our effective sample size by 7-12%. Single-variant analyses identified ten handgrip strength loci among African-Americans: four rare variants, five low-frequency variants, and one common variant. One significant and four suggestive genes were identified associated with handgrip strength when aggregating rare and functional variants; all associations were ancestry-specific. We additionally leveraged the different ancestries available in the UK Biobank to further explore the ancestry-specific association signals from the single-variant association analyses. In conclusion, our study identified 11 new loci associated with handgrip strength with rare and/or ancestry-specific genetic variations, highlighting the added value of whole-genome sequencing in diverse samples. Several of the associations identified using single-variant or aggregate analyses lie in genes with a function relevant to the brain or muscle or were reported to be associated with muscle or age-related traits. Further studies in samples with sequence data and diverse ancestries are needed to confirm these findings.

Identification of putative causal loci in whole-genome sequencing data via knockoff statistics. - He, Zihuai; Liu, Linxi; Wang, Chen; Le Guen, Yann; Lee, Justin; Gogarten, Stephanie; Lu, Fred; Montgomery, Stephen; Tang, Hua; Silverman, Edwin K; Cho, Michael H; Greicius, Michael; et al. (Nat Commun, 2021)
The analysis of whole-genome sequencing studies is challenging due to the large number of rare variants in noncoding regions and the lack of natural units for testing. We propose a statistical method to detect and localize rare and common risk variants in whole-genome sequencing studies based on a recently developed knockoff framework. It can (1) prioritize causal variants over associations due to linkage disequilibrium thereby improving interpretability; (2) help distinguish the signal due to rare variants from shadow effects of significant common variants nearby; (3) integrate multiple knockoffs for improved power, stability, and reproducibility; and (4) flexibly incorporate state-of-the-art and future association tests to achieve the benefits proposed here. In applications to whole-genome sequencing data from the Alzheimer's Disease Sequencing Project (ADSP) and COPDGene samples from NHLBI Trans-Omics for Precision Medicine (TOPMed) Program we show that our method compared with conventional association tests can lead to substantially more discoveries.
Keywords: Algorithms; Causality; Computer Simulation; Data Interpretation, Statistical; Datasets as Topic; Genetic Loci; Genetic Predisposition to Disease; Genome, Human; Genome-Wide Association Study; Humans; Linkage Disequilibrium; Markov Chains; Models, Genetic; Polymorphism, Single Nucleotide; Reproducibility of Results; Whole Genome Sequencing

Longitudinal Plasma Measures of Trimethylamine N-Oxide and Risk of Atherosclerotic Cardiovascular Disease Events in Community-Based Older Adults. - Lee, Yujin; Nemet, Ina; Wang, Zeneng; Lai, Heidi T M; de Oliveira Otto, Marcia C; Lemaitre, Rozenn N; Fretts, Amanda M; Sotoodehnia, Nona; Budoff, Matthew; DiDonato, Joseph A; McKnight, Barbara; Tang, W H Wilson; et al. (J Am Heart Assoc, 2021)
Background Trimethylamine N-oxide (TMAO) is a gut microbiota-dependent metabolite of dietary choline, L-carnitine, and phosphatidylcholine-rich foods. On the basis of experimental studies and patients with prevalent disease, elevated plasma TMAO may increase risk of atherosclerotic cardiovascular disease (ASCVD). TMAO is also renally cleared and may interact with and causally contribute to renal dysfunction. Yet, how serial TMAO levels relate to incident and recurrent ASCVD in community-based populations and the potential mediating or modifying role of renal function are not established. Methods and Results We investigated associations of serial measures of plasma TMAO, assessed at baseline and 7 years, with incident and recurrent ASCVD in a community-based cohort of 4131 (incident) and 1449 (recurrent) older US adults. TMAO was measured using stable isotope dilution liquid chromatography-tandem mass spectrometry (laboratory coefficient of variation, <6%). Incident ASCVD (myocardial infarction, fatal coronary heart disease, stroke, sudden cardiac death, or other atherosclerotic death) was centrally adjudicated using medical records. Risk was assessed by multivariable Cox proportional hazards regression, including time-varying demographics, lifestyle factors, medical history, laboratory measures, and dietary habits. Potential mediating effects and interaction by estimated glomerular filtration rate (eGFR) were assessed. During prospective follow-up, 1766 incident and 897 recurrent ASCVD events occurred. After multivariable adjustment, higher levels of TMAO were associated with a higher risk of incident ASCVD, with extreme quintile hazard ratio (HR) compared with the lowest quintile=1.21 (95% CI, 1.02-1.42; -trend=0.029). This relationship appeared mediated or confounded by eGFR (eGFR-adjusted HR, 1.07; 95% CI, 0.90-1.27), as well as modified by eGFR (-interaction <0.001). High levels of TMAO were associated with higher incidence of ASCVD in the presence of impaired renal function (eGFR <60 mL/min per 1.73 m: HR, 1.56 [95% CI, 1.13-2.14]; -trend=0.007), but not normal or mildly reduced renal function (eGFR ≥60 mL/min per 1.73 m: HR, 1.03 [95% CI, 0.85-1.25]; -trend=0.668). Among individuals with prior ASCVD, TMAO associated with higher risk of recurrent ASCVD (HR, 1.25 [95% CI, 1.01-1.56]; -trend=0.009), without significant modification by eGFR. Conclusions In this large community-based cohort of older US adults, serial measures of TMAO were associated with higher risk of incident ASCVD, with apparent modification by presence of impaired renal function and with higher risk of recurrent ASCVD.

Meta-analyses identify DNA methylation associated with kidney function and damage. - Schlosser, Pascal; Tin, Adrienne; Matias-Garcia, Pamela R; Thio, Chris H L; Joehanes, Roby; Liu, Hongbo; Weihs, Antoine; Yu, Zhi; Hoppmann, Anselm; Grundner-Culemann, Franziska; Min, Josine L; Adeyemo, Adebowale A; et al. (Nat Commun, 2021)
Chronic kidney disease is a major public health burden. Elevated urinary albumin-to-creatinine ratio is a measure of kidney damage, and used to diagnose and stage chronic kidney disease. To extend the knowledge on regulatory mechanisms related to kidney function and disease, we conducted a blood-based epigenome-wide association study for estimated glomerular filtration rate (n = 33,605) and urinary albumin-to-creatinine ratio (n = 15,068) and detected 69 and seven CpG sites where DNA methylation was associated with the respective trait. The majority of these findings showed directionally consistent associations with the respective clinical outcomes chronic kidney disease and moderately increased albuminuria. Associations of DNA methylation with kidney function, such as CpGs at JAZF1, PELI1 and CHD2 were validated in kidney tissue. Methylation at PHRF1, LDB2, CSRNP1 and IRF5 indicated causal effects on kidney function. Enrichment analyses revealed pathways related to hemostasis and blood cell migration for estimated glomerular filtration rate, and immune cell activation and response for urinary albumin-to-creatinineratio-associated CpGs.
Keywords: Adult; Aged; CpG Islands; DNA Methylation; Female; Glomerular Filtration Rate; Humans; Interferon Regulatory Factors; Kidney; Kidney Function Tests; LIM Domain Proteins; Male; Membrane Proteins; Middle Aged; Renal Insufficiency, Chronic; Transcription Factors

Meta-analysis of epigenome-wide association studies of carotid intima-media thickness. - Portilla-Fernández, Eliana; Hwang, Shih-Jen; Wilson, Rory; Maddock, Jane; Hill, W David; Teumer, Alexander; Mishra, Pashupati P; Brody, Jennifer A; Joehanes, Roby; Ligthart, Symen; Ghanbari, Mohsen; Kavousi, Maryam; et al. (Eur J Epidemiol, 2021)
Common carotid intima-media thickness (cIMT) is an index of subclinical atherosclerosis that is associated with ischemic stroke and coronary artery disease (CAD). We undertook a cross-sectional epigenome-wide association study (EWAS) of measures of cIMT in 6400 individuals. Mendelian randomization analysis was applied to investigate the potential causal role of DNA methylation in the link between atherosclerotic cardiovascular risk factors and cIMT or clinical cardiovascular disease. The CpG site cg05575921 was associated with cIMT (beta = -0.0264, p value = 3.5 × 10) in the discovery panel and was replicated in replication panel (beta = -0.07, p value = 0.005). This CpG is located at chr5:81649347 in the intron 3 of the aryl hydrocarbon receptor repressor gene (AHRR). Our results indicate that DNA methylation at cg05575921 might be in the pathway between smoking, cIMT and stroke. Moreover, in a region-based analysis, 34 differentially methylated regions (DMRs) were identified of which a DMR upstream of ALOX12 showed the strongest association with cIMT (p value = 1.4 × 10). In conclusion, our study suggests that DNA methylation may play a role in the link between cardiovascular risk factors, cIMT and clinical cardiovascular disease.

Multi-Ancestry Genome-wide Association Study Accounting for Gene-Psychosocial Factor Interactions Identifies Novel Loci for Blood Pressure Traits. - Sun, Daokun; Richard, Melissa; Musani, Solomon K; Sung, Yun Ju; Winkler, Thomas W; Schwander, Karen; Chai, Jin Fang; Guo, Xiuqing; Kilpeläinen, Tuomas O; Vojinovic, Dina; Aschard, Hugues; Bartz, Traci M; et al. (HGG Adv, 2021)
Psychological and social factors are known to influence blood pressure (BP) and risk of hypertension and associated cardiovascular diseases. To identify novel BP loci, we carried out genome-wide association meta-analyses of systolic, diastolic, pulse, and mean arterial BP taking into account the interaction effects of genetic variants with three psychosocial factors: depressive symptoms, anxiety symptoms, and social support. Analyses were performed using a two-stage design in a sample of up to 128,894 adults from 5 ancestry groups. In the combined meta-analyses of Stages 1 and 2, we identified 59 loci (p value <5e-8), including nine novel BP loci. The novel associations were observed mostly with pulse pressure, with fewer observed with mean arterial pressure. Five novel loci were identified in African ancestry, and all but one showed patterns of interaction with at least one psychosocial factor. Functional annotation of the novel loci supports a major role for genes implicated in the immune response (), synaptic function and neurotransmission (), as well as genes previously implicated in neuropsychiatric or stress-related disorders (). These findings underscore the importance of considering psychological and social factors in gene discovery for BP, especially in non-European populations.

Multi-ancestry genome-wide gene-sleep interactions identify novel loci for blood pressure. - Wang, Heming; Noordam, Raymond; Cade, Brian E; Schwander, Karen; Winkler, Thomas W; Lee, Jiwon; Sung, Yun Ju; Bentley, Amy R; Manning, Alisa K; Aschard, Hugues; Kilpeläinen, Tuomas O; Ilkov, Marjan; et al. (Mol Psychiatry, 2021)
Long and short sleep duration are associated with elevated blood pressure (BP), possibly through effects on molecular pathways that influence neuroendocrine and vascular systems. To gain new insights into the genetic basis of sleep-related BP variation, we performed genome-wide gene by short or long sleep duration interaction analyses on four BP traits (systolic BP, diastolic BP, mean arterial pressure, and pulse pressure) across five ancestry groups in two stages using 2 degree of freedom (df) joint test followed by 1df test of interaction effects. Primary multi-ancestry analysis in 62,969 individuals in stage 1 identified three novel gene by sleep interactions that were replicated in an additional 59,296 individuals in stage 2 (stage 1 + 2 P < 5 × 10), including rs7955964 (FIGNL2/ANKRD33) that increases BP among long sleepers, and rs73493041 (SNORA26/C9orf170) and rs10406644 (KCTD15/LSM14A) that increase BP among short sleepers (P < 5 × 10). Secondary ancestry-specific analysis identified another novel gene by long sleep interaction at rs111887471 (TRPC3/KIAA1109) in individuals of African ancestry (P = 2 × 10). Combined stage 1 and 2 analyses additionally identified significant gene by long sleep interactions at 10 loci including MKLN1 and RGL3/ELAVL3 previously associated with BP, and significant gene by short sleep interactions at 10 loci including C2orf43 previously associated with BP (P < 10). 2df test also identified novel loci for BP after modeling sleep that has known functions in sleep-wake regulation, nervous and cardiometabolic systems. This study indicates that sleep and primary mechanisms regulating BP may interact to elevate BP level, suggesting novel insights into sleep-related BP regulation.

{A multi-ethnic epigenome-wide association study of leukocyte DNA methylation and blood lipids - Jhun, M. A.; Mendelson, M.; Wilson, R.; Gondalia, R.; Joehanes, R.; Salfati, E.; Zhao, X.; Braun, K. V. E.; Do, A. N.; Hedman, Å. K.; Zhang, T.; Carnero-Montoro, E.; et al. (Nat Commun, 2021)
10.1038/s41467-021-23899-yHere we examine the association between DNA methylation in circulating leukocytes and blood lipids in a multi-ethnic sample of 16,265 subjects. We identify 148, 35, and 4 novel associations among Europeans, African Americans, and Hispanics, respectively, and an additional 186 novel associations through a trans-ethnic meta-analysis. We observe a high concordance in the direction of effects across racial/ethnic groups, a high correlation of effect sizes between high-density lipoprotein and triglycerides, a modest overlap of associations with epigenome-wide association studies of other cardio-metabolic traits, and a largely non-overlap with lipid loci identified to date through genome-wide association studies. Thirty CpGs reached significance in at least 2 racial/ethnic groups including 7 that showed association with the expression of an annotated gene. CpGs annotated to CPT1A showed evidence of being influenced by triglycerides levels. DNA methylation levels of circulating leukocytes show robust and consistent association with blood lipid levels across multiple racial/ethnic groups.

Multiethnic Genome-Wide Association Study of Subclinical Atherosclerosis in Individuals With Type 2 Diabetes. - Lu, Yingchang; Dimitrov, Latchezar; Chen, Shyh-Huei; Bielak, Lawrence F; Bis, Joshua C; Feitosa, Mary F; Lu, Lingyi; Kavousi, Maryam; Raffield, Laura M; Smith, Albert V; Wang, Lihua; Weiss, Stefan; et al. (Circ Genom Precis Med, 2021)
BACKGROUND: Coronary artery calcification (CAC) and carotid artery intima-media thickness (cIMT) are measures of subclinical atherosclerosis in asymptomatic individuals and strong risk factors for cardiovascular disease. Type 2 diabetes (T2D) is an independent cardiovascular disease risk factor that accelerates atherosclerosis. METHODS: We performed meta-analyses of genome-wide association studies in up to 2500 T2D individuals of European ancestry (EA) and 1590 T2D individuals of African ancestry with or without exclusion of prevalent cardiovascular disease, for CAC measured by cardiac computed tomography, and 3608 individuals of EA and 838 individuals of African ancestry with T2D for cIMT measured by ultrasonography within the CHARGE (Cohorts for Heart and Aging Research in Genomic Epidemiology) Consortium. RESULTS: We replicated 2 loci (rs9369640 and rs9349379 near and rs10757278 near ) for CAC and one locus for cIMT (rs7412 and rs445925 near ) that were previously reported in the general EA populations. We identified one novel CAC locus (rs8000449 near at 13q13.3) at =2.0×10 in EA. No additional loci were identified with the meta-analyses of EA and African ancestry. The expression quantitative trait loci analysis with nearby expressed genes derived from arterial wall and metabolic tissues from the Genotype-Tissue Expression project pinpoints , encoding a matricellular protein involved in bone formation and bone matrix organization, as the potential candidate gene at this locus. In addition, we found significant associations (<3.1×10) for 3 previously reported coronary artery disease loci for these subclinical atherosclerotic phenotypes (rs2891168 near and rs11170820 near for CAC, and rs7412 near for cIMT). CONCLUSIONS: Our results provide potential biological mechanisms that could link CAC and cIMT to increased cardiovascular disease risk in individuals with T2D.

is mutated in clonal hematopoiesis and myelodysplastic syndromes and impacts RNA splicing. - Beauchamp, Ellen M; Leventhal, Matthew; Bernard, Elsa; Hoppe, Emma R; Todisco, Gabriele; Creignou, Maria; Gallì, Anna; Castellano, Cecilia A; McConkey, Marie; Tarun, Akansha; Wong, Waihay; Schenone, Monica; et al. (Blood Cancer Discov, 2021)
Clonal hematopoiesis results from somatic mutations in cancer driver genes in hematopoietic stem cells. We sought to identify novel drivers of clonal expansion using an unbiased analysis of sequencing data from 84,683 persons and identified common mutations in the 5-methylcytosine reader, , as well as in , , and . We also identified these mutations at low frequency in myelodysplastic syndrome patients. edited mouse hematopoietic stem and progenitor cells exhibited a competitive advantage and increased genome-wide intron retention. mutations potentially link DNA methylation and RNA splicing, the two most commonly mutated pathways in clonal hematopoiesis and MDS.

n-3 Fatty Acid Biomarkers and Incident Type 2 Diabetes: An Individual Participant-Level Pooling Project of 20 Prospective Cohort Studies - Qian, F.; Ardisson Korat, A. V.; Imamura, F.; Marklund, M.; Tintle, N.; Virtanen, J. K.; Zhou, X.; Bassett, J. K.; Lai, H.; Hirakawa, Y.; Chien, K. L.; Wood, A. C.; et al. (Diabetes Care, 2021)
-linolenic acid (ALA), eicosapentaenoic acid (EPA), docosapentaenoic acid (DPA), and docosahexaenoic acid (DHA) with T2D risk through an individual participant-level pooled analysis.\ For our analysis we incorporated data from a global consortium of 20 prospective studies from 14 countries. We included 65,147 participants who had blood measurements of ALA, EPA, DPA, or DHA and were free of diabetes at baseline. De novo harmonized analyses were performed in each cohort following a prespecified protocol, and cohort-specific associations were pooled using inverse variance-weighted meta-analysis.\ 0.001). ALA was not associated with T2D (HR 0.97 [95% CI 0.92, 1.02]) per interquintile range. Associations were robust across prespecified subgroups as well as in sensitivity analyses.\ Higher circulating biomarkers of seafood-derived n-3 fatty acids, including EPA, DPA, DHA, and their sum, were associated with lower risk of T2D in a global consortium of prospective studies. The biomarker of plant-derived ALA was not significantly associated with T2D risk.

Nonesterified Fatty Acids and Kidney Function Decline in Older Adults: Findings From the Cardiovascular Health Study. - Walther, Carl P; Ix, Joachim H; Biggs, Mary L; Kizer, Jorge R; Navaneethan, Sankar D; Djoussé, Luc; Mukamal, Kenneth J (Am J Kidney Dis, 2021)
RATIONALE & OBJECTIVE: Circulating non-esterified fatty acids (NEFAs) make up a small portion of circulating lipids but are a metabolically important energy source. Excessive circulating NEFAs may contribute to lipotoxicity in many tissues, including the kidneys. We investigated the relationship between total circulating NEFA concentration and kidney outcomes in older, community-dwelling adults. STUDY DESIGN: Prospective cohort study. SETTING & PARTICIPANTS: 4,698 participants ≥65 years of age in the Cardiovascular Health Study who underwent total fasting serum NEFA concentration measurements in 1992-1993. EXPOSURE: Fasting serum NEFA concentration at one timepoint. OUTCOMES: Three primary outcomes: estimated glomerular filtration rate (eGFR) decline of >30%; the composite of eGFR decline ≥30% or kidney failure with replacement therapy (KFRT); and change in eGFR. These outcomes were assessed over 4- and 13-year periods. ANALYTICAL APPROACH: Logistic regression for the dichotomous outcomes and mixed effects models for the continuous outcome, with sequential adjustment for baseline covariates. Inverse probability of attrition weighting was implemented to account for informative attrition during the follow-up periods. RESULTS: Serum NEFA concentrations were not independently associated with kidney outcomes. In unadjusted and partially adjusted analyses, the highest quartile of serum NEFA concentration (compared to lowest) was associated with a higher risk of ≥30% eGFR decline at 4 years and faster rate of decline of eGFR. No associations were evident after adjustment for comorbidities, lipid levels, insulin sensitivity, medications, and vital signs: odds ratio 1.33 (95%CI 0.83-2.13); estimated glomerular filtration rate change per year, Q4 vs Q1: -0.15 ml/min/1.73m/year (95%CI -0.36 to 0.06). LIMITATIONS: Single NEFA measurements, no measurements of post-glucose load NEFA concentrations or individual NEFA species, no measurement of baseline urine albumin. CONCLUSIONS: A single fasting serum NEFA concentration was not independently associated with long-term adverse kidney outcomes in a cohort of older community-living adults.

Performance of the American Heart Association/American College of Cardiology Pooled Cohort Equations to Estimate Atherosclerotic Cardiovascular Disease Risk by Self-reported Physical Activity Levels. - Pandey, Ambarish; Mehta, Anurag; Paluch, Amanda; Ning, Hongyan; Carnethon, Mercedes R; Allen, Norrina B; Michos, Erin D; Berry, Jarett D; Lloyd-Jones, Donald M; Wilkins, John T (JAMA Cardiol, 2021)
Importance: The American Heart Association/American College of Cardiology pooled cohort equations (PCEs) are used for predicting 10-year atherosclerotic cardiovascular disease (ASCVD) risk. Pooled cohort equation risk prediction capabilities across self-reported leisure-time physical activity (LTPA) levels and the change in model performance with addition of LTPA to the PCE are unclear. Objective: To evaluate PCE risk prediction performance across self-reported LTPA levels and the change in model performance by adding LTPA to the existing PCE model. Design, Setting, and Participants: Individual-level pooling of data from 3 longitudinal cohort studies-Atherosclerosis Risk in Communities, Multi-Ethnic Study of Atherosclerosis, and Cardiovascular Health Study-was performed. A total of 18 824 participants were stratified into 4 groups based on self-reported LTPA levels: inactive (0 metabolic equivalent of task [MET]-min/wk), less than guideline-recommended (<500 MET-min/wk), guideline-recommended (500-1000 MET-min/week), and greater than guideline-recommended (>1000 MET-min/wk). Pooled cohort equation risk discrimination was studied using the C statistic and reclassification capabilities were studied using the Greenwood Nam-D'Agostino χ2 goodness-of-fit test. Change in risk discrimination and reclassification on adding LTPA to PCEs was evaluated using change in C statistic, integrated discrimination index, and categorical net reclassification index. Main Outcomes and Measures: Adjudicated ASCVD events during 10-year follow-up. Results: Among 18 824 participants studied, 10 302 were women (54.7%); mean (SD) age was 57.6 (8.2) years. A total of 5868 participants (31.2%) were inactive, 3849 (20.4%) had less than guideline-recommended LTPA, 3372 (17.9%) had guideline-recommended LTPA, and 5735 (30.5%) had greater than guideline-recommended LTPA level. Higher LTPA levels were associated with a lower risk of ASCVD after adjustment for risk factors (hazard ratio [HR] per 1-SD higher LTPA, 0.91; 95% CI, 0.86-0.96). Across LTPA groups, PCE risk discrimination (C statistic, 0.76-0.78) and risk calibration (all χ2﻿ P > .10) was similar. Addition of LTPA to the PCE model resulted in no significant change in the C statistic (0.0005; 95% CI, -0.0004 to 0.0015; P = .28) and categorical net reclassification index (-0.003; 95% CI, -0.010 to 0.010; P = .95), but a minimal improvement in the integrated discrimination index (0.0008; 95% CI, 0.0002-0.0013; P = .005) was observed. Similar results were noted when cohort-specific coefficients were used for creating the baseline model. Conclusions and Relevance: Higher self-reported LTPA levels appear to be associated with lower ASCVD risk and increasing LTPA promotes cardiovascular wellness. These findings suggest the American Heart Association/American College of Cardiology PCEs are accurate at estimating the probability of 10-year ASCVD risk regardless of LTPA level. The addition of self-reported LTPA to PCEs does not appear to be associated with improvement in risk prediction model performance.

The Pharmacogenetics of Statin Therapy on Clinical Events: No Evidence that Genetic Variation Affects Statin Response on Myocardial Infarction. - Trompet, Stella; Postmus, Iris; Warren, Helen R; Noordam, Raymond; Smit, Roelof A J; Theusch, Elizabeth; Li, Xiaohui; Arsenault, Benoit; Chasman, Daniel I; Hitman, Graham A; Munroe, Patricia B; Rotter, Jerome I; et al. (Front Pharmacol, 2021)
The pharmacogenetic effect on cardiovascular disease reduction in response to statin treatment has only been assessed in small studies. In a pharmacogenetic genome wide association study (GWAS) analysis within the Genomic Investigation of Statin Therapy (GIST) consortium, we investigated whether genetic variation was associated with the response of statins on cardiovascular disease risk reduction. The investigated endpoint was incident myocardial infarction (MI) defined as coronary heart disease death and definite and suspect non-fatal MI. For imputed single nucleotide polymorphisms (SNPs), regression analysis was performed on expected allelic dosage and meta-analysed with a fixed-effects model, inverse variance weighted meta-analysis. All SNPs with -values <5.0 × 10 in stage 1 GWAS meta-analysis were selected for further investigation in stage-2. As a secondary analysis, we extracted SNPs from the Stage-1 GWAS meta-analysis results based on predefined hypotheses to possibly modifying the effect of statin therapy on MI. In stage-1 meta-analysis (eight studies, = 10,769, 4,212 cases), we observed no genome-wide significant results ( < 5.0 × 10). A total of 144 genetic variants were followed-up in the second stage (three studies, = 1,525, 180 cases). In the combined meta-analysis, no genome-wide significant hits were identified. Moreover, none of the look-ups of SNPs known to be associated with either CHD or with statin response to cholesterol levels reached Bonferroni level of significance within our stage-1 meta-analysis. This GWAS analysis did not provide evidence that genetic variation affects statin response on cardiovascular risk reduction. It does not appear likely that genetic testing for predicting effects of statins on clinical events will become a useful tool in clinical practice.

Physical Function and Survival in Older Adults: A longitudinal study accounting for time-varying effects. - Karunananthan, Sathya; Moodie, Erica E M; Bergman, Howard; Payette, Hélène; Diehr, Paula H; Wolfson, Christina (Arch Gerontol Geriatr, 2021)
PURPOSE OF THE STUDY: Variation in physical function in older adults over time raises several methodological challenges in the study of its association with survival, many of which have largely been overlooked in previous studies. The objective of this study is to examine the relationship between time-varying measures of physical function and survival in men and women aged 70 years and over, while accounting for the time-varying effects of health and lifestyle characteristics. METHODS: 1,846 women and 1,245 men in the Cardiovascular Health Study followed annually for up to 10 years beginning at age 70-74 years were included. We estimated the effect of gait speed and grip strength on survival over the subsequent year, using age as the timescale. RESULTS: A 0.1m/s higher gait speed was associated with a 12% decrease in the likelihood of death in the subsequent year among women (HR 0.88, 95% CI 0.82-0.94). There was no statistically significant effect of gait speed on survival among men (HR 0.97, 95% CI 0.91 to 1.03), or of grip strength on survival among women (HR 0.97, 95% CI 0.95-1.00) or men (HR 0.99, 95% CI 0.97-1.01), over one year. CONCLUSIONS: Upon using time-varying measures of physical function while accounting for time-varying effects of health and lifestyle characteristics, higher gait speed was associated with increased survival among the women in our study. We found no evidence of an association between gait speed and one-year survival in men, or between grip strength and one-year survival in women or men.

{The power of genetic diversity in genome-wide association studies of lipids - Graham, S. E.; Clarke, S. L.; Wu, K. H.; Kanoni, S.; Zajac, G. J. M.; Ramdas, S.; Surakka, I.; Ntalla, I.; Vedantam, S.; Winkler, T. W.; Locke, A. E.; Marouli, E.; et al. (Nature, 2021)
application of polygenic scores in clinical practice.

Pre-Statistical Considerations for Harmonization of Cognitive Instruments: Harmonization of ARIC, CARDIA, CHS, FHS, MESA, and NOMAS. - Briceño, Emily M; Gross, Alden L; Giordani, Bruno J; Manly, Jennifer J; Gottesman, Rebecca F; Elkind, Mitchell S V; Sidney, Stephen; Hingtgen, Stephanie; Sacco, Ralph L; Wright, Clinton B; Fitzpatrick, Annette; Fohner, Alison E; et al. (J Alzheimers Dis, 2021)
BACKGROUND: Meta-analyses of individuals' cognitive data are increasing to investigate the biomedical, lifestyle, and sociocultural factors that influence cognitive decline and dementia risk. Pre-statistical harmonization of cognitive instruments is a critical methodological step for accurate cognitive data harmonization, yet specific approaches for this process are unclear. OBJECTIVE: To describe pre-statistical harmonization of cognitive instruments for an individual-level meta-analysis in the blood pressure and cognition (BP COG) study. METHODS: We identified cognitive instruments from six cohorts (the Atherosclerosis Risk in Communities Study, Cardiovascular Health Study, Coronary Artery Risk Development in Young Adults study, Framingham Offspring Study, Multi-Ethnic Study of Atherosclerosis, and Northern Manhattan Study) and conducted an extensive review of each item's administration and scoring procedures, and score distributions. RESULTS: We included 153 cognitive instrument items from 34 instruments across the six cohorts. Of these items, 42%were common across ≥2 cohorts. 86%of common items showed differences across cohorts. We found administration, scoring, and coding differences for seemingly equivalent items. These differences corresponded to variability across cohorts in score distributions and ranges. We performed data augmentation to adjust for differences. CONCLUSION: Cross-cohort administration, scoring, and procedural differences for cognitive instruments are frequent and need to be assessed to address potential impact on meta-analyses and cognitive data interpretation. Detecting and accounting for these differences is critical for accurate attributions of cognitive health across cohort studies.

{Rare and low-frequency exonic variants and gene-by-smoking interactions in pulmonary function - Yang, T.; Jackson, V. E.; Smith, A. V.; Chen, H.; Bartz, T. M.; Sitlani, C. M.; Psaty, B. M.; Gharib, S. A.; O'Connor, G. T.; Dupuis, J.; Xu, J.; Lohman, K.; et al. (Sci Rep, 2021)
. This study investigates the utility of assessing gene-by-smoking interactions and underscores their effects on potential pulmonary function.

{Rare Coding Variants Associated With Electrocardiographic Intervals Identify Monogenic Arrhythmia Susceptibility Genes: A Multi-Ancestry Analysis - Choi, S. H.; Jurgens, S. J.; Haggerty, C. M.; Hall, A. W.; Halford, J. L.; Morrill, V. N.; Weng, L. C.; Lagerman, B.; Mirshahi, T.; Pettinger, M.; Guo, X.; Lin, H. J.; et al. (Circ Genom Precis Med, 2021)
Alterations in electrocardiographic (ECG) intervals are well-known markers for arrhythmia and sudden cardiac death (SCD) risk. While the genetics of arrhythmia syndromes have been studied, relations between electrocardiographic intervals and rare genetic variation at a population level are poorly understood.\ Using a discovery sample of 29 000 individuals with whole-genome sequencing from Trans-Omics in Precision Medicine and replication in nearly 100 000 with whole-exome sequencing from the UK Biobank and MyCode, we examined associations between low-frequency and rare coding variants with 5 routinely measured electrocardiographic traits (RR, P-wave, PR, and QRS intervals and corrected QT interval).\ ), a marker of SCD risk. Incomplete penetrance of such deleterious variation was common as over 70% of carriers had normal electrocardiographic intervals.\ Our findings indicate that large-scale high-depth sequence data and electrocardiographic analysis identifies monogenic arrhythmia susceptibility genes and rare variants with large effects. Known pathogenic variation in conventional arrhythmia and SCD genes exhibited incomplete penetrance and accounted for only a small fraction of marked electrocardiographic interval prolongation.

Sequencing of 53,831 diverse genomes from the NHLBI TOPMed Program. - Taliun, Daniel; Harris, Daniel N; Kessler, Michael D; Carlson, Jedidiah; Szpiech, Zachary A; Torres, Raul; Taliun, Sarah A Gagliano; Corvelo, André; Gogarten, Stephanie M; Kang, Hyun Min; Pitsillides, Achilleas N; LeFaive, Jonathon; et al. (Nature, 2021)
The Trans-Omics for Precision Medicine (TOPMed) programme seeks to elucidate the genetic architecture and biology of heart, lung, blood and sleep disorders, with the ultimate goal of improving diagnosis, treatment and prevention of these diseases. The initial phases of the programme focused on whole-genome sequencing of individuals with rich phenotypic data and diverse backgrounds. Here we describe the TOPMed goals and design as well as the available resources and early insights obtained from the sequence data. The resources include a variant browser, a genotype imputation server, and genomic and phenotypic data that are available through dbGaP (Database of Genotypes and Phenotypes). In the first 53,831 TOPMed samples, we detected more than 400 million single-nucleotide and insertion or deletion variants after alignment with the reference genome. Additional previously undescribed variants were detected through assembly of unmapped reads and customized analysis in highly variable loci. Among the more than 400 million detected variants, 97% have frequencies of less than 1% and 46% are singletons that are present in only one individual (53% among unrelated individuals). These rare variants provide insights into mutational processes and recent human evolutionary history. The extensive catalogue of genetic variation in TOPMed studies provides unique opportunities for exploring the contributions of rare and noncoding sequence variants to phenotypic variation. Furthermore, combining TOPMed haplotypes with modern imputation methods improves the power and reach of genome-wide association studies to include variants down to a frequency of approximately 0.01%.

Sex Differences in Cognitive Decline Among US Adults. - Levine, Deborah A; Gross, Alden L; Briceño, Emily M; Tilton, Nicholas; Giordani, Bruno J; Sussman, Jeremy B; Hayward, Rodney A; Burke, James F; Hingtgen, Stephanie; Elkind, Mitchell S V; Manly, Jennifer J; Gottesman, Rebecca F; et al. (JAMA Netw Open, 2021)
Importance: Sex differences in dementia risk are unclear, but some studies have found greater risk for women. Objective: To determine associations between sex and cognitive decline in order to better understand sex differences in dementia risk. Design, Setting, and Participants: This cohort study used pooled analysis of individual participant data from 5 cohort studies for years 1971 to 2017: Atherosclerosis Risk in Communities Study, Coronary Artery Risk Development in Young Adults Study, Cardiovascular Health Study, Framingham Offspring Study, and Northern Manhattan Study. Linear mixed-effects models were used to estimate changes in each continuous cognitive outcome over time by sex. Data analysis was completed from March 2019 to October 2020. Exposure: Sex. Main Outcomes and Measures: The primary outcome was change in global cognition. Secondary outcomes were change in memory and executive function. Outcomes were standardized as t scores (mean [SD], 50 [10]); a 1-point difference represents a 0.1-SD difference in cognition. Results: Among 34 349 participants, 26 088 who self-reported Black or White race, were free of stroke and dementia, and had covariate data at or before the first cognitive assessment were included for analysis. Median (interquartile range) follow-up was 7.9 (5.3-20.5) years. There were 11 775 (44.7%) men (median [interquartile range] age, 58 [51-66] years at first cognitive assessment; 2229 [18.9%] Black) and 14 313 women (median [interquartile range] age, 58 [51-67] years at first cognitive assessment; 3636 [25.4%] Black). Women had significantly higher baseline performance than men in global cognition (2.20 points higher; 95% CI, 2.04 to 2.35 points; P < .001), executive function (2.13 points higher; 95% CI, 1.98 to 2.29 points; P < .001), and memory (1.89 points higher; 95% CI, 1.72 to 2.06 points; P < .001). Compared with men, women had significantly faster declines in global cognition (-0.07 points/y faster; 95% CI, -0.08 to -0.05 points/y; P < .001) and executive function (-0.06 points/y faster; 95% CI, -0.07 to -0.05 points/y; P < .001). Men and women had similar declines in memory (-0.004 points/y faster; 95% CI, -0.023 to 0.014; P = .61). Conclusions and Relevance: The results of this cohort study suggest that women may have greater cognitive reserve but faster cognitive decline than men, which could contribute to sex differences in late-life dementia.
Keywords: Aged; Cognitive Dysfunction; Cognitive Reserve; Cohort Studies; Executive Function; Humans; Memory; Middle Aged; Risk; Sex Factors; Time Factors; United States

{Sex-dimorphic genetic effects and novel loci for fasting glucose and insulin variability - Lagou, V.; Mägi, R.; Hottenga, J. J.; Grallert, H.; Perry, J. R. B.; Bouatia-Naji, N.; Marullo, L.; Rybin, D.; Jansen, R.; Min, J. L.; Dimas, A. S.; Ulrich, A.; et al. (Nat Commun, 2021)
Differences between sexes contribute to variation in the levels of fasting glucose and insulin. Epidemiological studies established a higher prevalence of impaired fasting glucose in men and impaired glucose tolerance in women, however, the genetic component underlying this phenomenon is not established. We assess sex-dimorphic (73,089/50,404 women and 67,506/47,806 men) and sex-combined (151,188/105,056 individuals) fasting glucose/fasting insulin genetic effects via genome-wide association study meta-analyses in individuals of European descent without diabetes. Here we report sex dimorphism in allelic effects on fasting insulin at IRS1 and ZNF12 loci, the latter showing higher RNA expression in whole blood in women compared to men. We also observe sex-homogeneous effects on fasting glucose at seven novel loci. Fasting insulin in women shows stronger genetic correlations than in men with waist-to-hip ratio and anorexia nervosa. Furthermore, waist-to-hip ratio is causally related to insulin resistance in women, but not in men. These results position dissection of metabolic and glycemic health sex dimorphism as a steppingstone for understanding differences in genetic effects between women and men in related phenotypes.

{Sex-dimorphic genetic effects and novel loci for fasting glucose and insulin variability - Lagou, V.; M?gi, R.; Hottenga, J. J.; Grallert, H.; Perry, J. R. B.; Bouatia-Naji, N.; Marullo, L.; Rybin, D.; Jansen, R.; Min, J. L.; Dimas, A. S.; Ulrich, A.; et al. (Nat Commun, 2021)
Differences between sexes contribute to variation in the levels of fasting glucose and insulin. Epidemiological studies established a higher prevalence of impaired fasting glucose in men and impaired glucose tolerance in women, however, the genetic component underlying this phenomenon is not established. We assess sex-dimorphic (73,089/50,404 women and 67,506/47,806 men) and sex-combined (151,188/105,056 individuals) fasting glucose/fasting insulin genetic effects via genome-wide association study meta-analyses in individuals of European descent without diabetes. Here we report sex dimorphism in allelic effects on fasting insulin at IRS1 and ZNF12 loci, the latter showing higher RNA expression in whole blood in women compared to men. We also observe sex-homogeneous effects on fasting glucose at seven novel loci. Fasting insulin in women shows stronger genetic correlations than in men with waist-to-hip ratio and anorexia nervosa. Furthermore, waist-to-hip ratio is causally related to insulin resistance in women, but not in men. These results position dissection of metabolic and glycemic health sex dimorphism as a steppingstone for understanding differences in genetic effects between women and men in related phenotypes.

Sugar-Sweetened Beverage Consumption May Modify Associations Between Genetic Variants in the CHREBP (Carbohydrate Responsive Element Binding Protein) Locus and HDL-C (High-Density Lipoprotein Cholesterol) and Triglyceride Concentrations. - Haslam, Danielle E; Peloso, Gina M; Guirette, Melanie; Imamura, Fumiaki; Bartz, Traci M; Pitsillides, Achilleas N; Wang, Carol A; Li-Gao, Ruifang; Westra, Jason M; Pitkänen, Niina; Young, Kristin L; Graff, Mariaelisa; et al. (Circ Genom Precis Med, 2021)
BACKGROUND: ChREBP (carbohydrate responsive element binding protein) is a transcription factor that responds to sugar consumption. Sugar-sweetened beverage (SSB) consumption and genetic variants in the locus have separately been linked to HDL-C (high-density lipoprotein cholesterol) and triglyceride concentrations. We hypothesized that SSB consumption would modify the association between genetic variants in the locus and dyslipidemia. METHODS: Data from 11 cohorts from the Cohorts for Heart and Aging Research in Genomic Epidemiology consortium (N=63 599) and the UK Biobank (N=59 220) were used to quantify associations of SSB consumption, genetic variants, and their interaction on HDL-C and triglyceride concentrations using linear regression models. A total of 1606 single nucleotide polymorphisms within or near were considered. SSB consumption was estimated from validated questionnaires, and participants were grouped by their estimated intake. RESULTS: In a meta-analysis, rs71556729 was significantly associated with higher HDL-C concentrations only among the highest SSB consumers (β, 2.12 [95% CI, 1.16-3.07] mg/dL per allele; <0.0001), but not significantly among the lowest SSB consumers (=0.81; <0.0001). Similar results were observed for 2 additional variants (rs35709627 and rs71556736). For triglyceride, rs55673514 was positively associated with triglyceride concentrations only among the highest SSB consumers (β, 0.06 [95% CI, 0.02-0.09] ln-mg/dL per allele, =0.001) but not the lowest SSB consumers (=0.84; =0.0005). CONCLUSIONS: Our results identified genetic variants in the locus that may protect against SSB-associated reductions in HDL-C and other variants that may exacerbate SSB-associated increases in triglyceride concentrations. Registration: URL: https://www.clinicaltrials.gov; Unique identifier: NCT00005133, NCT00005121, NCT00005487, and NCT00000479.

Supplemental Association of Clonal Hematopoiesis With Incident Heart Failure. - Yu, Bing; Roberts, Mary B; Raffield, Laura M; Zekavat, Seyedeh Maryam; Nguyen, Ngoc Quynh H; Biggs, Mary L; Brown, Michael R; Griffin, Gabriel; Desai, Pinkal; Correa, Adolfo; Morrison, Alanna C; Shah, Amil M; et al. (J Am Coll Cardiol, 2021)
BACKGROUND: Age-related clonal hematopoiesis of indeterminate potential (CHIP), defined as clonally expanded leukemogenic sequence variations (particularly in DNMT3A, TET2, ASXL1, and JAK2) in asymptomatic individuals, is associated with cardiovascular events, including recurrent heart failure (HF). OBJECTIVES: This study sought to evaluate whether CHIP is associated with incident HF. METHODS: CHIP status was obtained from whole exome or genome sequencing of blood DNA in participants without prevalent HF or hematological malignancy from 5 cohorts. Cox proportional hazards models were performed within each cohort, adjusting for demographic and clinical risk factors, followed by fixed-effect meta-analyses. Large CHIP clones (defined as variant allele frequency >10%), HF with or without baseline coronary heart disease, and left ventricular ejection fraction were evaluated in secondary analyses. RESULTS: Of 56,597 individuals (59% women, mean age 58 years at baseline), 3,406 (6%) had CHIP, and 4,694 developed HF (8.3%) over up to 20 years of follow-up. CHIP was prospectively associated with a 25% increased risk of HF in meta-analysis (hazard ratio: 1.25; 95% confidence interval: 1.13-1.38) with consistent associations across cohorts. ASXL1, TET2, and JAK2 sequence variations were each associated with an increased risk of HF, whereas DNMT3A sequence variations were not associated with HF. Secondary analyses suggested large CHIP was associated with a greater risk of HF (hazard ratio: 1.29; 95% confidence interval: 1.15-1.44), and the associations for CHIP on HF with and without prior coronary heart disease were homogenous. ASXL1 sequence variations were associated with reduced left ventricular ejection fraction. CONCLUSIONS: CHIP, particularly sequence variations in ASXL1, TET2, and JAK2, represents a new risk factor for HF.
Keywords: Aged; Clonal Hematopoiesis; Correlation of Data; Demography; DNA-Binding Proteins; Female; Heart Failure; Humans; Janus Kinase 2; Male; Middle Aged; Mutation; Proportional Hazards Models; Proto-Oncogene Proteins; Repressor Proteins; Risk Factors; Stroke Volume; Ventricular Dysfunction, Left; Whole Exome Sequencing

A System for Phenotype Harmonization in the NHLBI Trans-Omics for Precision Medicine (TOPMed) Program. - Stilp, Adrienne M; Emery, Leslie S; Broome, Jai G; Buth, Erin J; Khan, Alyna T; Laurie, Cecelia A; Wang, Fei Fei; Wong, Quenna; Chen, Dongquan; D'Augustine, Catherine M; Heard-Costa, Nancy L; Hohensee, Chancellor R; et al. (Am J Epidemiol, 2021)
Genotype-phenotype association studies often combine phenotype data from multiple studies to increase power. Harmonization of the data usually requires substantial effort due to heterogeneity in phenotype definitions, study design, data collection procedures, and data set organization. Here we describe a centralized system for phenotype harmonization that includes input from phenotype domain and study experts, quality control, documentation, reproducible results, and data sharing mechanisms. This system was developed for the National Heart, Lung and Blood Institute's Trans-Omics for Precision Medicine program, which is generating genomic and other omics data for >80 studies with extensive phenotype data. To date, 63 phenotypes have been harmonized across thousands of participants from up to 17 studies per phenotype (participants recruited 1948-2012). We discuss challenges in this undertaking and how they were addressed. The harmonized phenotype data and associated documentation have been submitted to National Institutes of Health data repositories for controlled-access by the scientific community. We also provide materials to facilitate future harmonization efforts by the community, which include (1) the code used to generate the 63 harmonized phenotypes, enabling others to reproduce, modify or extend these harmonizations to additional studies; and (2) results of labeling thousands of phenotype variables with controlled vocabulary terms.

{The trans-ancestral genomic architecture of glycemic traits - Chen, J.; Spracklen, C. N.; Marenne, G.; Varshney, A.; Corbin, L. J.; Luan, J.; Willems, S. M.; Wu, Y.; Zhang, X.; Horikoshi, M.; Boutin, T. S.; Mägi, R.; et al. (Nat Genet, 2021)
10.1038/s41588-021-00852-9Glycemic traits are used to diagnose and monitor type 2 diabetes and cardiometabolic health. To date, most genetic studies of glycemic traits have focused on individuals of European ancestry. Here we aggregated genome-wide association studies comprising up to 281,416 individuals without diabetes (30% non-European ancestry) for whom fasting glucose, 2-h glucose after an oral glucose challenge, glycated hemoglobin and fasting insulin data were available. Trans-ancestry and single-ancestry meta-analyses identified 242 loci (99 novel; P < 5 × 10-8), 80% of which had no significant evidence of between-ancestry heterogeneity. Analyses restricted to individuals of European ancestry with equivalent sample size would have led to 24 fewer new loci. Compared with single-ancestry analyses, equivalent-sized trans-ancestry fine-mapping reduced the number of estimated variants in 99% credible sets by a median of 37.5%. Genomic-feature, gene-expression and gene-set analyses revealed distinct biological signatures for each trait, highlighting different underlying biological pathways. Our results increase our understanding of diabetes pathophysiology by using trans-ancestry studies for improved power and resolution.

Whole genome sequence analyses of eGFR in 23,732 people representing multiple ancestries in the NHLBI trans-omics for precision medicine (TOPMed) consortium. - Lin, Bridget M; Grinde, Kelsey E; Brody, Jennifer A; Breeze, Charles E; Raffield, Laura M; Mychaleckyj, Josyf C; Thornton, Timothy A; Perry, James A; Baier, Leslie J; de Las Fuentes, Lisa; Guo, Xiuqing; Heavner, Benjamin D; et al. (EBioMedicine, 2021)
BACKGROUND: Genetic factors that influence kidney traits have been understudied for low frequency and ancestry-specific variants. METHODS: We combined whole genome sequencing (WGS) data from 23,732 participants from 10 NHLBI Trans-Omics for Precision Medicine (TOPMed) Program multi-ethnic studies to identify novel loci for estimated glomerular filtration rate (eGFR). Participants included European, African, East Asian, and Hispanic ancestries. We applied linear mixed models using a genetic relationship matrix estimated from the WGS data and adjusted for age, sex, study, and ethnicity. FINDINGS: When testing single variants, we identified three novel loci driven by low frequency variants more commonly observed in non-European ancestry (PRKAA2, rs180996919, minor allele frequency [MAF] 0.04%, P = 6.1 × 10; METTL8, rs116951054, MAF 0.09%, P = 4.5 × 10; and MATK, rs539182790, MAF 0.05%, P = 3.4 × 10). We also replicated two known loci for common variants (rs2461702, MAF=0.49, P = 1.2 × 10, nearest gene GATM, and rs71147340, MAF=0.34, P = 3.3 × 10, CDK12). Testing aggregated variants within a gene identified the MAF gene. A statistical approach based on local ancestry helped to identify replication samples for ancestry-specific variants. INTERPRETATION: This study highlights challenges in studying variants influencing kidney traits that are low frequency in populations and more common in non-European ancestry.

Whole genome sequence analysis of platelet traits in the NHLBI trans-omics for precision medicine initiative. - Little, Amarise; Hu, Yao; Sun, Quan; Jain, Deepti; Broome, Jai; Chen, Ming-Huei; Thibord, Florian; McHugh, Caitlin; Surendran, Praveen; Blackwell, Thomas W; Brody, Jennifer A; Bhan, Arunoday; et al. (Hum Mol Genet, 2021)
Platelets play a key role in thrombosis and hemostasis. Platelet count (PLT) and mean platelet volume (MPV) are highly heritable quantitative traits, with hundreds of genetic signals previously identified, mostly in European ancestry populations. We here utilize whole genome sequencing from NHLBI's Trans-Omics for Precision Medicine Initiative (TOPMed) in a large multi-ethnic sample to further explore common and rare variation contributing to PLT (n = 61 200) and MPV (n = 23 485). We identified and replicated secondary signals at MPL (rs532784633) and PECAM1 (rs73345162), both more common in African ancestry populations. We also observed rare variation in Mendelian platelet related disorder genes influencing variation in platelet traits in TOPMed cohorts (not enriched for blood disorders). For example, association of GP9 with lower PLT and higher MPV was partly driven by a pathogenic Bernard-Soulier syndrome variant (rs5030764, p.Asn61Ser), and the signals at TUBB1 and CD36 were partly driven by loss of function variants not annotated as pathogenic in ClinVar (rs199948010 and rs571975065). However, residual signal remained for these gene-based signals after adjusting for lead variants, suggesting that additional variants in Mendelian genes with impacts in general population cohorts remain to be identified. Gene-based signals were also identified at several GWAS identified loci for genes not annotated for Mendelian platelet disorders (PTPRH, TET2, CHEK2), with somatic variation driving the result at TET2. These results highlight the value of whole genome sequencing in populations of diverse genetic ancestry to identify novel regulatory and coding signals, even for well-studied traits like platelet traits.

Whole-genome association analyses of sleep-disordered breathing phenotypes in the NHLBI TOPMed program. - Cade, Brian E; Lee, Jiwon; Sofer, Tamar; Wang, Heming; Zhang, Man; Chen, Han; Gharib, Sina A; Gottlieb, Daniel J; Guo, Xiuqing; Lane, Jacqueline M; Liang, Jingjing; Lin, Xihong; et al. (Genome Med, 2021)
BACKGROUND: Sleep-disordered breathing is a common disorder associated with significant morbidity. The genetic architecture of sleep-disordered breathing remains poorly understood. Through the NHLBI Trans-Omics for Precision Medicine (TOPMed) program, we performed the first whole-genome sequence analysis of sleep-disordered breathing. METHODS: The study sample was comprised of 7988 individuals of diverse ancestry. Common-variant and pathway analyses included an additional 13,257 individuals. We examined five complementary traits describing different aspects of sleep-disordered breathing: the apnea-hypopnea index, average oxyhemoglobin desaturation per event, average and minimum oxyhemoglobin saturation across the sleep episode, and the percentage of sleep with oxyhemoglobin saturation < 90%. We adjusted for age, sex, BMI, study, and family structure using MMSKAT and EMMAX mixed linear model approaches. Additional bioinformatics analyses were performed with MetaXcan, GIGSEA, and ReMap. RESULTS: We identified a multi-ethnic set-based rare-variant association (p = 3.48 × 10) on chromosome X with ARMCX3. Additional rare-variant associations include ARMCX3-AS1, MRPS33, and C16orf90. Novel common-variant loci were identified in the NRG1 and SLC45A2 regions, and previously associated loci in the IL18RAP and ATP2B4 regions were associated with novel phenotypes. Transcription factor binding site enrichment identified associations with genes implicated with respiratory and craniofacial traits. Additional analyses identified significantly associated pathways. CONCLUSIONS: We have identified the first gene-based rare-variant associations with objectively measured sleep-disordered breathing traits. Our results increase the understanding of the genetic architecture of sleep-disordered breathing and highlight associations in genes that modulate lung development, inflammation, respiratory rhythmogenesis, and HIF1A-mediated hypoxic response.

Whole-genome sequencing association analysis of quantitative red blood cell phenotypes: The NHLBI TOPMed program. - Hu, Yao; Stilp, Adrienne M; McHugh, Caitlin P; Rao, Shuquan; Jain, Deepti; Zheng, Xiuwen; Lane, John; Méric de Bellefon, Sébastian; Raffield, Laura M; Chen, Ming-Huei; Yanek, Lisa R; Wheeler, Marsha; et al. (Am J Hum Genet, 2021)
Whole-genome sequencing (WGS), a powerful tool for detecting novel coding and non-coding disease-causing variants, has largely been applied to clinical diagnosis of inherited disorders. Here we leveraged WGS data in up to 62,653 ethnically diverse participants from the NHLBI Trans-Omics for Precision Medicine (TOPMed) program and assessed statistical association of variants with seven red blood cell (RBC) quantitative traits. We discovered 14 single variant-RBC trait associations at 12 genomic loci, which have not been reported previously. Several of the RBC trait-variant associations (RPN1, ELL2, MIDN, HBB, HBA1, PIEZO1, and G6PD) were replicated in independent GWAS datasets imputed to the TOPMed reference panel. Most of these discovered variants are rare/low frequency, and several are observed disproportionately among non-European Ancestry (African, Hispanic/Latino, or East Asian) populations. We identified a 3 bp indel p.Lys2169del (g.88717175_88717177TCT[4]) (common only in the Ashkenazi Jewish population) of PIEZO1, a gene responsible for the Mendelian red cell disorder hereditary xerocytosis (MIM: 194380), associated with higher mean corpuscular hemoglobin concentration (MCHC). In stepwise conditional analysis and in gene-based rare variant aggregated association analysis, we identified several of the variants in HBB, HBA1, TMPRSS6, and G6PD that represent the carrier state for known coding, promoter, or splice site loss-of-function variants that cause inherited RBC disorders. Finally, we applied base and nuclease editing to demonstrate that the sentinel variant rs112097551 (nearest gene RPN1) acts through a cis-regulatory element that exerts long-range control of the gene RUVBL1 which is essential for hematopoiesis. Together, these results demonstrate the utility of WGS in ethnically diverse population-based samples and gene editing for expanding knowledge of the genetic architecture of quantitative hematologic traits and suggest a continuum between complex trait and Mendelian red cell disorders.
Keywords: Adult; Aged; Chromosomes, Human, Pair 16; Datasets as Topic; Erythrocytes; Female; Gene Editing; Genetic Variation; Genome-Wide Association Study; HEK293 Cells; Humans; Male; Middle Aged; National Heart, Lung, and Blood Institute (U.S.); Phenotype; Quality Control; Reproducibility of Results; United States

Whole-genome sequencing in diverse subjects identifies genetic correlates of leukocyte traits: The NHLBI TOPMed program. - Mikhaylova, Anna V; McHugh, Caitlin P; Polfus, Linda M; Raffield, Laura M; Boorgula, Meher Preethi; Blackwell, Thomas W; Brody, Jennifer A; Broome, Jai; Chami, Nathalie; Chen, Ming-Huei; Conomos, Matthew P; Cox, Corey; et al. (Am J Hum Genet, 2021)
Many common and rare variants associated with hematologic traits have been discovered through imputation on large-scale reference panels. However, the majority of genome-wide association studies (GWASs) have been conducted in Europeans, and determining causal variants has proved challenging. We performed a GWAS of total leukocyte, neutrophil, lymphocyte, monocyte, eosinophil, and basophil counts generated from 109,563,748 variants in the autosomes and the X chromosome in the Trans-Omics for Precision Medicine (TOPMed) program, which included data from 61,802 individuals of diverse ancestry. We discovered and replicated 7 leukocyte trait associations, including (1) the association between a chromosome X, pseudo-autosomal region (PAR), noncoding variant located between cytokine receptor genes (CSF2RA and CLRF2) and lower eosinophil count; and (2) associations between single variants found predominantly among African Americans at the S1PR3 (9q22.1) and HBB (11p15.4) loci and monocyte and lymphocyte counts, respectively. We further provide evidence indicating that the newly discovered eosinophil-lowering chromosome X PAR variant might be associated with reduced susceptibility to common allergic diseases such as atopic dermatitis and asthma. Additionally, we found a burden of very rare FLT3 (13q12.2) variants associated with monocyte counts. Together, these results emphasize the utility of whole-genome sequencing in diverse samples in identifying associations missed by European-ancestry-driven GWASs.
Keywords: Asthma; Biomarkers; Dermatitis, Atopic; Genetic Predisposition to Disease; Genome, Human; Genome-Wide Association Study; Humans; Leukocytes; National Heart, Lung, and Blood Institute (U.S.); Phenotype; Polymorphism, Single Nucleotide; Prognosis; Proteome; Pulmonary Disease, Chronic Obstructive; Quantitative Trait Loci; United Kingdom; United States; Whole Genome Sequencing

Assessing the contribution of rare variants to complex trait heritability from whole-genome sequence data. - Wainschtein, Pierrick; Jain, Deepti; Zheng, Zhili; Cupples, L Adrienne; Shadyab, Aladdin H; McKnight, Barbara; Shoemaker, Benjamin M; Mitchell, Braxton D; Psaty, Bruce M; Kooperberg, Charles; Liu, Ching-Ti; Albert, Christine M; et al. (Nat Genet, 2022)
Analyses of data from genome-wide association studies on unrelated individuals have shown that, for human traits and diseases, approximately one-third to two-thirds of heritability is captured by common SNPs. However, it is not known whether the remaining heritability is due to the imperfect tagging of causal variants by common SNPs, in particular whether the causal variants are rare, or whether it is overestimated due to bias in inference from pedigree data. Here we estimated heritability for height and body mass index (BMI) from whole-genome sequence data on 25,465 unrelated individuals of European ancestry. The estimated heritability was 0.68 (standard error 0.10) for height and 0.30 (standard error 0.10) for body mass index. Low minor allele frequency variants in low linkage disequilibrium (LD) with neighboring variants were enriched for heritability, to a greater extent for protein-altering variants, consistent with negative selection. Our results imply that rare variants, in particular those in regions of low linkage disequilibrium, are a major source of the still missing heritability of complex traits and disease.

Association of Trimethylamine N-Oxide and Metabolites With Mortality in Older Adults. - Fretts, Amanda M; Hazen, Stanley L; Jensen, Paul; Budoff, Matthew; Sitlani, Colleen M; Wang, Meng; de Oliveira Otto, Marcia C; DiDonato, Joseph A; Lee, Yujin; Psaty, Bruce M; Siscovick, David S; Sotoodehnia, Nona; et al. (JAMA Netw Open, 2022)
Importance: Little is known about the association of trimethylamine N-oxide (TMAO), a novel plasma metabolite derived from L-carnitine and phosphatidylcholine, and related metabolites (ie, choline, betaine, carnitine, and butyrobetaine) with risk of death among older adults in the general population. Objective: To investigate the associations of serial measures of plasma TMAO and related metabolites with risk of total and cause-specific death (ie, deaths from cardiovascular diseases [CVDs] and non-CVDs) among older adults in the US. Design, Setting, and Participants: This prospective cohort study involved 5333 participants from the Cardiovascular Health Study-a community-based longitudinal cohort of adults aged 65 years or older-who were followed up from June 1, 1989, to December 31, 2015. Participants were from 4 communities in the US (Forsyth County, North Carolina; Sacramento County, California; Washington County, Maryland; and Allegheny County, Pennsylvania). Data were analyzed from March 17 to June 23, 2021. Exposures: Plasma TMAO, choline, betaine, carnitine, and butyrobetaine levels were measured using stored samples from baseline (June 1, 1989, to May 31, 1990, or November 1, 1992, to June 31, 1993) and follow-up examination (June 1, 1996, to May 31, 1997). Measurements were performed through stable-isotope dilution liquid chromatography with tandem mass spectrometry using high-performance liquid chromatography with online electrospray ionization tandem mass spectrometry. Main Outcomes and Measures: Deaths (total and cause specific) were adjudicated by a centralized Cardiovascular Health Study events committee based on information from medical records, laboratory and diagnostic reports, death certificates, and/or interviews with next of kin. The associations of each metabolite with mortality were assessed using Cox proportional hazards regression models. Results: Among 5333 participants in the analytic sample, the mean (SD) age was 73 (6) years; 2149 participants (40.3%) were male, 3184 (59.7%) were female, 848 (15.9%) were African American, 4450 (83.4%) were White, and 35 (0.01%) were of other races (12 were American Indian or Alaska Native, 4 were Asian or Pacific Islander, and 19 were of other races or ethnicities). During a median follow-up of 13.2 years (range, 0-26.9 years), 4791 deaths occurred. After adjustment for potential confounders, the hazard ratios for death from any cause (ie, total mortality) comparing extreme quintiles (fifth vs first) of plasma concentrations were 1.30 (95% CI, 1.17-1.44) for TMAO, 1.19 (95% CI, 1.08-1.32) for choline, 1.26 (95% CI, 1.15-1.40) for carnitine, and 1.26 (95% CI, 1.13-1.40) for butyrobetaine. Plasma betaine was not associated with risk of death. The extent of risk estimates was similar for CVD and non-CVD mortality. Conclusions and Relevance: In this cohort study, plasma concentrations of TMAO and related metabolites were positively associated with risk of death. These findings suggest that circulating TMAO is an important novel risk factor associated with death among older adults.
Keywords: Aged; Betaine; Cardiovascular Diseases; Carnitine; Choline; Cohort Studies; Female; Humans; Male; Methylamines; Prospective Studies

{An association test of the spatial distribution of rare missense variants within protein structures identifies Alzheimer's disease-related patterns - Jin, B.; Capra, J. A.; Benchek, P.; Wheeler, N.; Naj, A. C.; Hamilton-Nelson, K. L.; Farrell, J. J.; Leung, Y. Y.; Kunkle, B.; Vadarajan, B.; Schellenberg, G. D.; Mayeux, R.; et al. (Genome Res, 2022)
is a novel AD risk gene that has a cluster of variants primarily shared by case subjects around the Sec6 domain. This cluster is also validated in an independent replication data set and a validation data set with a larger sample size.

Associations between Alcohol Consumption and HDL Subspecies Defined by ApoC3, ApoE and ApoJ: the Cardiovascular Health Study. - Wilkens, Trine L; Sørensen, Helle; Jensen, Majken K; Furtado, Jeremy D; Dragsted, Lars O; Mukamal, Kenneth J (Curr Probl Cardiol, 2022)
Alcohol consumption increases circulating high-density lipoprotein cholesterol (HDL-C), but HDL protein cargo may better reflect HDL function. This study examined the associations between alcohol intake and HDL subspecies containing or lacking apoC3, apoE, and apoJ in a well-phenotyped cohort. We performed a cross-sectional analysis of 2092 Cardiovascular Health Study participants aged 70 or older with HDL subspecies measured in stored specimens from 1998 to 1999. Associations between alcohol intake and apoA1 defined HDL subspecies lacking or containing apoC3, apoE, and apoJ, and circulating levels of total apoA1, apoC3, apoE, and apoJ were examined. HDL subspecies lacking and containing apoC3, apoE, and apoJ were all positively associated with alcohol intake, with ∼1% per additional drink per week or ∼7% per additional drink per day (subspecies without the apolipoproteins, P ≤ 2 × 10, subspecies with the apolipoproteins, P ≤ 3 × 10). Total apoA1 was also directly associated with alcohol consumption, with a 1% increase per additional drink per week (P = 1 × 10). Total apoC3 blood levels were 0.5% higher per additional drink per week (P = 0.01), but the association was driven by a few heavily drinking men. Alcohol intake was positively associated with HDL subspecies lacking and containing apoC3, apoE, or apoJ, and with total plasma apoA1. ApoC3 was directly, albeit not as robustly associated with alcohol intake. HDL protein cargo is crucial for its anti-atherosclerotic functions, but it remains to be determined whether HDL subspecies play a role in the putative association between limited alcohol intake and lower risk of coronary heart disease.

Associations of Pulmonary Function with MRI Brain Volumes: A Coordinated Multi-Study Analysis. - Frenzel, Stefan; Bis, Josh C; Gudmundsson, Elias F; O'Donnell, Adrienne; Simino, Jeannette; Yaqub, Amber; Bartz, Traci M; Brusselle, Guy G O; Bülow, Robin; DeCarli, Charles S; Ewert, Ralf; Gharib, Sina A; et al. (J Alzheimers Dis, 2022)
BACKGROUND: Previous studies suggest poor pulmonary function is associated with increased burden of cerebral white matter hyperintensities and brain atrophy among elderly individuals, but the results are inconsistent. OBJECTIVE: To study the cross-sectional associations of pulmonary function with structural brain variables. METHODS: Data from six large community-based samples (N = 11,091) were analyzed. Spirometric measurements were standardized with respect to age, sex, height, and ethnicity using reference equations of the Global Lung Function Initiative. Associations of forced expiratory volume in 1 s (FEV1), forced vital capacity (FVC), and their ratio FEV1/FVC with brain volume, gray matter volume, hippocampal volume, and volume of white matter hyperintensities were investigated using multivariable linear regressions for each study separately and then combined using random-effect meta-analyses. RESULTS: FEV1 and FVC were positively associated with brain volume, gray matter volume, and hippocampal volume, and negatively associated with white matter hyperintensities volume after multiple testing correction, with little heterogeneity present between the studies. For instance, an increase of FVC by one unit was associated with 3.5 ml higher brain volume (95% CI: [2.2, 4.9]). In contrast, results for FEV1/FVC were more heterogeneous across studies, with significant positive associations with brain volume, gray matter volume, and hippocampal volume, but not white matter hyperintensities volume. Associations of brain variables with both FEV1 and FVC were consistently stronger than with FEV1/FVC, specifically with brain volume and white matter hyperintensities volume. CONCLUSION: In cross-sectional analyses, worse pulmonary function is associated with smaller brain volumes and higher white matter hyperintensities burden.

Clonal Hematopoiesis Is Associated With Higher Risk of Stroke. - Bhattacharya, Romit; Zekavat, Seyedeh M; Haessler, Jeffrey; Fornage, Myriam; Raffield, Laura; Uddin, Md Mesbah; Bick, Alexander G; Niroula, Abhishek; Yu, Bing; Gibson, Christopher; Griffin, Gabriel; Morrison, Alanna C; et al. (Stroke, 2022)
BACKGROUND AND PURPOSE: Clonal hematopoiesis of indeterminate potential (CHIP) is a novel age-related risk factor for cardiovascular disease-related morbidity and mortality. The association of CHIP with risk of incident ischemic stroke was reported previously in an exploratory analysis including a small number of incident stroke cases without replication and lack of stroke subphenotyping. The purpose of this study was to discover whether CHIP is a risk factor for ischemic or hemorrhagic stroke. METHODS: We utilized plasma genome sequence data of blood DNA to identify CHIP in 78 752 individuals from 8 prospective cohorts and biobanks. We then assessed the association of CHIP and commonly mutated individual CHIP driver genes (, , and ) with any stroke, ischemic stroke, and hemorrhagic stroke. RESULTS: CHIP was associated with an increased risk of total stroke (hazard ratio, 1.14 [95% CI, 1.03-1.27]; =0.01) after adjustment for age, sex, and race. We observed associations with CHIP with risk of hemorrhagic stroke (hazard ratio, 1.24 [95% CI, 1.01-1.51]; =0.04) and with small vessel ischemic stroke subtypes. In gene-specific association results, showed the strongest association with total stroke and ischemic stroke, whereas and were each associated with increased risk of hemorrhagic stroke. CONCLUSIONS: CHIP is associated with an increased risk of stroke, particularly with hemorrhagic and small vessel ischemic stroke. Future studies clarifying the relationship between CHIP and subtypes of stroke are needed.

{Clonal hematopoiesis of indeterminate potential, DNA methylation, and risk for coronary artery disease - Uddin, M. D. M.; Nguyen, N. Q. H.; Yu, B.; Brody, J. A.; Pampana, A.; Nakao, T.; Fornage, M.; Bressler, J.; Sotoodehnia, N.; Weinstock, J. S.; Honigberg, M. C.; Nachun, D.; et al. (Nat Commun, 2022)
Age-related changes to the genome-wide DNA methylation (DNAm) pattern observed in blood are well-documented. Clonal hematopoiesis of indeterminate potential (CHIP), characterized by the age-related acquisition and expansion of leukemogenic mutations in hematopoietic stem cells (HSCs), is associated with blood cancer and coronary artery disease (CAD). Epigenetic regulators DNMT3A and TET2 are the two most frequently mutated CHIP genes. Here, we present results from an epigenome-wide association study for CHIP in 582 Cardiovascular Health Study (CHS) participants, with replication in 2655 Atherosclerosis Risk in Communities (ARIC) Study participants. We show that DNMT3A and TET2 CHIP have distinct and directionally opposing genome-wide DNAm association patterns consistent with their regulatory roles, albeit both promoting self-renewal of HSCs. Mendelian randomization analyses indicate that a subset of DNAm alterations associated with these two leading CHIP genes may promote the risk for CAD.

Cross-Ancestry Investigation of Venous Thromboembolism Genomic Predictors. - Thibord, Florian; Klarin, Derek; Brody, Jennifer A; Chen, Ming-Huei; Levin, Michael G; Chasman, Daniel I; Goode, Ellen L; Hveem, Kristian; Teder-Laving, Maris; Martinez-Perez, Angel; Aïssi, Dylan; Daian-Bacq, Delphine; et al. (Circulation, 2022)
BACKGROUND: Venous thromboembolism (VTE) is a life-threatening vascular event with environmental and genetic determinants. Recent VTE genome-wide association studies (GWAS) meta-analyses involved nearly 30 000 VTE cases and identified up to 40 genetic loci associated with VTE risk, including loci not previously suspected to play a role in hemostasis. The aim of our research was to expand discovery of new genetic loci associated with VTE by using cross-ancestry genomic resources. METHODS: We present new cross-ancestry meta-analyzed GWAS results involving up to 81 669 VTE cases from 30 studies, with replication of novel loci in independent populations and loci characterization through in silico genomic interrogations. RESULTS: In our genetic discovery effort that included 55 330 participants with VTE (47 822 European, 6320 African, and 1188 Hispanic ancestry), we identified 48 novel associations, of which 34 were replicated after correction for multiple testing. In our combined discovery-replication analysis (81 669 VTE participants) and ancestry-stratified meta-analyses (European, African, and Hispanic), we identified another 44 novel associations, which are new candidate VTE-associated loci requiring replication. In total, across all GWAS meta-analyses, we identified 135 independent genomic loci significantly associated with VTE risk. A genetic risk score of the significantly associated loci in Europeans identified a 6-fold increase in risk for those in the top 1% of scores compared with those with average scores. We also identified 31 novel transcript associations in transcriptome-wide association studies and 8 novel candidate genes with protein quantitative-trait locus Mendelian randomization analyses. In silico interrogations of hemostasis and hematology traits and a large phenome-wide association analysis of the 135 GWAS loci provided insights to biological pathways contributing to VTE, with some loci contributing to VTE through well-characterized coagulation pathways and others providing new data on the role of hematology traits, particularly platelet function. Many of the replicated loci are outside of known or currently hypothesized pathways to thrombosis. CONCLUSIONS: Our cross-ancestry GWAS meta-analyses identified new loci associated with VTE. These findings highlight new pathways to thrombosis and provide novel molecules that may be useful in the development of improved antithrombosis treatments.
Keywords: Genetic Predisposition to Disease; Genome-Wide Association Study; Genomics; Humans; Polymorphism, Single Nucleotide; Quantitative Trait Loci; Thrombosis; Venous Thromboembolism

Dietary Meat, Trimethylamine N-Oxide-Related Metabolites, and Incident Cardiovascular Disease Among Older Adults: The Cardiovascular Health Study. - Wang, Meng; Wang, Zeneng; Lee, Yujin; Lai, Heidi T M; de Oliveira Otto, Marcia C; Lemaitre, Rozenn N; Fretts, Amanda; Sotoodehnia, Nona; Budoff, Matthew; DiDonato, Joseph A; McKnight, Barbara; Tang, W H Wilson; et al. (Arterioscler Thromb Vasc Biol, 2022)
BACKGROUND: Effects of animal source foods (ASF) on atherosclerotic cardiovascular disease (ASCVD) and underlying mechanisms remain controversial. We investigated prospective associations of different ASF with incident ASCVD and potential mediation by gut microbiota-generated trimethylamine N-oxide, its L-carnitine-derived intermediates γ-butyrobetaine and crotonobetaine, and traditional ASCVD risk pathways. METHODS: Among 3931 participants from a community-based US cohort aged 65+ years, ASF intakes and trimethylamine N-oxide-related metabolites were measured serially over time. Incident ASCVD (myocardial infarction, fatal coronary heart disease, stroke, other atherosclerotic death) was adjudicated over 12.5 years median follow-up. Cox proportional hazards models with time-varying exposures and covariates examined ASF-ASCVD associations; and additive hazard models, mediation proportions by different risk pathways. RESULTS: After multivariable-adjustment, higher intakes of unprocessed red meat, total meat, and total ASF associated with higher ASCVD risk, with hazard ratios (95% CI) per interquintile range of 1.15 (1.01-1.30), 1.22 (1.07-1.39), and 1.18 (1.03-1.34), respectively. Trimethylamine N-oxide-related metabolites together significantly mediated these associations, with mediation proportions (95% CI) of 10.6% (1.0-114.5), 7.8% (1.0-32.7), and 9.2% (2.2-44.5), respectively. Processed meat intake associated with a nonsignificant trend toward higher ASCVD (1.11 [0.98-1.25]); intakes of fish, poultry, and eggs were not significantly associated. Among other risk pathways, blood glucose, insulin, and C-reactive protein, but not blood pressure or blood cholesterol, each significantly mediated the total meat-ASCVD association. CONCLUSIONS: In this large, community-based cohort, higher meat intake associated with incident ASCVD, partly mediated by microbiota-derived metabolites of L-carnitine, abundant in red meat. These novel findings support biochemical links between dietary meat, gut microbiome pathways, and ASCVD.
Keywords: Animals; Atherosclerosis; Cardiovascular Diseases; Carnitine; Humans; Meat; Methylamines; Risk Factors

Differential and shared genetic effects on kidney function between diabetic and non-diabetic individuals. - Winkler, Thomas W; Rasheed, Humaira; Teumer, Alexander; Gorski, Mathias; Rowan, Bryce X; Stanzick, Kira J; Thomas, Laurent F; Tin, Adrienne; Hoppmann, Anselm; Chu, Audrey Y; Tayo, Bamidele; Thio, Chris H L; et al. (Commun Biol, 2022)
Reduced glomerular filtration rate (GFR) can progress to kidney failure. Risk factors include genetics and diabetes mellitus (DM), but little is known about their interaction. We conducted genome-wide association meta-analyses for estimated GFR based on serum creatinine (eGFR), separately for individuals with or without DM (n = 178,691, n = 1,296,113). Our genome-wide searches identified (i) seven eGFR loci with significant DM/noDM-difference, (ii) four additional novel loci with suggestive difference and (iii) 28 further novel loci (including CUBN) by allowing for potential difference. GWAS on eGFR among DM individuals identified 2 known and 27 potentially responsible loci for diabetic kidney disease. Gene prioritization highlighted 18 genes that may inform reno-protective drug development. We highlight the existence of DM-only and noDM-only effects, which can inform about the target group, if respective genes are advanced as drug targets. Largely shared effects suggest that most drug interventions to alter eGFR should be effective in DM and noDM.
Keywords: Creatinine; Diabetes Mellitus; Diabetic Nephropathies; Genome-Wide Association Study; Glomerular Filtration Rate; Humans; Kidney

{DNA methylation signature of chronic low-grade inflammation and its role in cardio-respiratory diseases - Wielscher, M.; Mandaviya, P. R.; Kuehnel, B.; Joehanes, R.; Mustafa, R.; Robinson, O.; Zhang, Y.; Bodinier, B.; Walton, E.; Mishra, P. P.; Schlosser, P.; Wilson, R.; et al. (Nat Commun, 2022)
We performed a multi-ethnic Epigenome Wide Association study on 22,774 individuals to describe the DNA methylation signature of chronic low-grade inflammation as measured by C-Reactive protein (CRP). We find 1,511 independent differentially methylated loci associated with CRP. These CpG sites show correlation structures across chromosomes, and are primarily situated in euchromatin, depleted in CpG islands. These genomic loci are predominantly situated in transcription factor binding sites and genomic enhancer regions. Mendelian randomization analysis suggests altered CpG methylation is a consequence of increased blood CRP levels. Mediation analysis reveals obesity and smoking as important underlying driving factors for changed CpG methylation. Finally, we find that an activated CpG signature significantly increases the risk for cardiometabolic diseases and COPD.

Endophenotype effect sizes support variant pathogenicity in monogenic disease susceptibility genes. - Halford, Jennifer L; Morrill, Valerie N; Choi, Seung Hoan; Jurgens, Sean J; Melloni, Giorgio; Marston, Nicholas A; Weng, Lu-Chen; Nauffal, Victor; Hall, Amelia W; Gunn, Sophia; Austin-Tse, Christina A; Pirruccello, James P; et al. (Nat Commun, 2022)
Accurate and efficient classification of variant pathogenicity is critical for research and clinical care. Using data from three large studies, we demonstrate that population-based associations between rare variants and quantitative endophenotypes for three monogenic diseases (low-density-lipoprotein cholesterol for familial hypercholesterolemia, electrocardiographic QTc interval for long QT syndrome, and glycosylated hemoglobin for maturity-onset diabetes of the young) provide evidence for variant pathogenicity. Effect sizes are associated with pathogenic ClinVar assertions (P < 0.001 for each trait) and discriminate pathogenic from non-pathogenic variants (area under the curve 0.82-0.84 across endophenotypes). An effect size threshold of ≥ 0.5 times the endophenotype standard deviation nominates up to 35% of rare variants of uncertain significance or not in ClinVar in disease susceptibility genes with pathogenic potential. We propose that variant associations with quantitative endophenotypes for monogenic diseases can provide evidence supporting pathogenicity.
Keywords: Disease Susceptibility; Endophenotypes; Humans; Long QT Syndrome; Virulence

Epigenetic and integrative cross-omics analyses of cerebral white matter hyperintensities on MRI. - Yang, Yunju; Knol, Maria J; Wang, Ruiqi; Mishra, Aniket; Liu, Dan; Luciano, Michelle; Teumer, Alexander; Armstrong, Nicola; Bis, Joshua C; Jhun, Min A; Li, Shuo; Adams, Hieab H H; et al. (Brain, 2022)
Cerebral white matter hyperintensities on MRI are markers of cerebral small vessel disease, a major risk factor for dementia and stroke. Despite the successful identification of multiple genetic variants associated with this highly heritable condition, its genetic architecture remains incompletely understood. More specifically, the role of DNA methylation has received little attention. We investigated the association between white matter hyperintensity burden and DNA methylation in blood at approximately 450,000 CpG sites in 9,732 middle-aged to older adults from 14 community-based studies. Single-CpG and region-based association analyses were carried out. Functional annotation and integrative cross-omics analyses were performed to identify novel genes underlying the relationship between DNA methylation and white matter hyperintensities. We identified 12 single-CpG and 46 region-based DNA methylation associations with white matter hyperintensity burden. Our top discovery single CpG, cg24202936 (P = 7.6 × 10-8), was associated with F2 expression in blood (P = 6.4 × 10-5), and colocalized with FOLH1 expression in brain (posterior probability =0.75). Our top differentially methylated regions were in PRMT1 and in CCDC144NL-AS1, which were also represented in single-CpG associations (cg17417856 and cg06809326, respectively). Through Mendelian randomization analyses cg06809326 was putatively associated with white matter hyperintensity burden (P = 0.03) and expression of CCDC144NL-AS1 possibly mediated this association. Differentially methylated region analysis, joint epigenetic association analysis, and multi-omics colocalization analysis consistently identified a role of DNA methylation near SH3PXD2A, a locus previously identified in genome-wide association studies of white matter hyperintensities. Gene set enrichment analyses revealed functions of the identified DNA methylation loci in the blood-brain barrier and in the immune response. Integrative cross-omics analysis identified 19 key regulatory genes in two networks related to extracellular matrix organization, and lipid and lipoprotein metabolism. A drug repositioning analysis indicated antihyperlipidemic agents, more specifically peroxisome proliferator-activated receptor alpha, as possible target drugs for white matter hyperintensities. Our epigenome-wide association study and integrative cross-omics analyses implicate novel genes influencing white matter hyperintensity burden, which converged on pathways related to the immune response and to a compromised blood brain barrier possibly due to disrupted cell-cell and cell-extracellular matrix interactions. The results also suggest that antihyperlipidemic therapy may contribute to lowering risk for white matter hyperintensities possibly through protection against blood brain barrier disruption.

A framework for detecting noncoding rare-variant associations of large-scale whole-genome sequencing studies. - Li, Zilin; Li, Xihao; Zhou, Hufeng; Gaynor, Sheila M; Selvaraj, Margaret Sunitha; Arapoglou, Theodore; Quick, Corbin; Liu, Yaowu; Chen, Han; Sun, Ryan; Dey, Rounak; Arnett, Donna K; et al. (Nat Methods, 2022)
Large-scale whole-genome sequencing studies have enabled analysis of noncoding rare-variant (RV) associations with complex human diseases and traits. Variant-set analysis is a powerful approach to study RV association. However, existing methods have limited ability in analyzing the noncoding genome. We propose a computationally efficient and robust noncoding RV association detection framework, STAARpipeline, to automatically annotate a whole-genome sequencing study and perform flexible noncoding RV association analysis, including gene-centric analysis and fixed window-based and dynamic window-based non-gene-centric analysis by incorporating variant functional annotations. In gene-centric analysis, STAARpipeline uses STAAR to group noncoding variants based on functional categories of genes and incorporate multiple functional annotations. In non-gene-centric analysis, STAARpipeline uses SCANG-STAAR to incorporate dynamic window sizes and multiple functional annotations. We apply STAARpipeline to identify noncoding RV sets associated with four lipid traits in 21,015 discovery samples from the Trans-Omics for Precision Medicine (TOPMed) program and replicate several of them in an additional 9,123 TOPMed samples. We also analyze five non-lipid TOPMed traits.
Keywords: Genetic Variation; Genome; Genome-Wide Association Study; Humans; Phenotype; Whole Genome Sequencing

{Gene Set Enrichment Analsyes Identify Pathways Involved in Genetic Risk for Diabetic Retinopathy - Sobrin, L.; Susarla, G.; Stanwyck, L.; Rouhana, J. M.; Li, A.; Pollack, S.; Igo, R. P.; Jensen, R. A.; Li, X.; Ng, M. C. Y.; Smith, A. V.; Kuo, J. Z.; et al. (Am J Ophthalmol, 2022)
{To identify functionally related genes associated with diabetic retinopathy (DR) risk using gene set enrichment analyses applied to genome-wide association study meta-analyses.\ .05.\ .05) in the other method. These pathways were regulation of the lipid catabolic process (2-fold enrichment

{Gene-mapping study of extremes of cerebral small vessel disease reveals TRIM47 as a strong candidate - Mishra, A.; Duplaà, C.; Vojinovic, D.; Suzuki, H.; Sargurupremraj, M.; Zilhao, N. R.; Li, S.; Bartz, T. M.; Jian, X.; Zhao, W.; Hofer, E.; Wittfeld, K.; et al. (Brain, 2022)
Cerebral small vessel disease is a leading cause of stroke and a major contributor to cognitive decline and dementia, but our understanding of specific genes underlying the cause of sporadic cerebral small vessel disease is limited. We report a genome-wide association study and a whole-exome association study on a composite extreme phenotype of cerebral small vessel disease derived from its most common MRI features: white matter hyperintensities and lacunes. Seventeen population-based cohorts of older persons with MRI measurements and genome-wide genotyping (n = 41 326), whole-exome sequencing (n = 15 965), or exome chip (n = 5249) data contributed 13 776 and 7079 extreme small vessel disease samples for the genome-wide association study and whole-exome association study, respectively. The genome-wide association study identified significant association of common variants in 11 loci with extreme small vessel disease, of which the chr12q24.11 locus was not previously reported to be associated with any MRI marker of cerebral small vessel disease. The whole-exome association study identified significant associations of extreme small vessel disease with common variants in the 5' UTR region of EFEMP1 (chr2p16.1) and one probably damaging common missense variant in TRIM47 (chr17q25.1). Mendelian randomization supports the causal association of extensive small vessel disease severity with increased risk of stroke and Alzheimer's disease. Combined evidence from summary-based Mendelian randomization studies and profiling of human loss-of-function allele carriers showed an inverse relation between TRIM47 expression in the brain and blood vessels and extensive small vessel disease severity. We observed significant enrichment of Trim47 in isolated brain vessel preparations compared to total brain fraction in mice, in line with the literature showing Trim47 enrichment in brain endothelial cells at single cell level. Functional evaluation of TRIM47 by small interfering RNAs-mediated knockdown in human brain endothelial cells showed increased endothelial permeability, an important hallmark of cerebral small vessel disease pathology. Overall, our comprehensive gene-mapping study and preliminary functional evaluation suggests a putative role of TRIM47 in the pathophysiology of cerebral small vessel disease, making it an important candidate for extensive in vivo explorations and future translational work.

{Genetic analyses of the electrocardiographic QT interval and its components identify additional loci and pathways - Young, W. J.; Lahrouchi, N.; Isaacs, A.; Duong, T.; Foco, L.; Ahmed, F.; Brody, J. A.; Salman, R.; Noordam, R.; Benjamins, J. W.; Haessler, J.; Lyytikäinen, L. P.; et al. (Nat Commun, 2022)
250,000 individuals) we identify 177, 156 and 121 independent loci for QT, JT and QRS, respectively, including a male-specific X-chromosome locus. Using gene-based rare-variant methods, we identify associations with Mendelian disease genes. Enrichments are observed in established pathways for QT and JT, and previously unreported genes indicated in insulin-receptor signalling and cardiac energy metabolism. In contrast for QRS, connective tissue components and processes for cell growth and extracellular matrix interactions are significantly enriched. We demonstrate polygenic risk score associations with atrial fibrillation, conduction disease and sudden cardiac death. Prioritization of druggable genes highlight potential therapeutic targets for arrhythmia. Together, these results substantially advance our understanding of the genetic architecture of ventricular depolarization and repolarization.

{Genetic and clinical determinants of abdominal aortic diameter: genome-wide association studies, exome array data and Mendelian randomization study - Portilla-Fernandez, E.; Klarin, D.; Hwang, S. J.; Biggs, M. L.; Bis, J. C.; Weiss, S.; Rospleszcz, S.; Natarajan, P.; Hoffmann, U.; Rogers, I. S.; Truong, Q. A.; lker, U.; et al. (Hum Mol Genet, 2022)
0.0001), known risk factors for AAA, consistent with a causal association with AAD. Our findings point to new biology as well as highlighting gene regions in mechanisms that have previously been implicated in the genetics of other vascular diseases.

Genetic loci and prioritization of genes for kidney function decline derived from a meta-analysis of 62 longitudinal genome-wide association studies. - Gorski, Mathias; Rasheed, Humaira; Teumer, Alexander; Thomas, Laurent F; Graham, Sarah E; Sveinbjornsson, Gardar; Winkler, Thomas W; Günther, Felix; Stark, Klaus J; Chai, Jin-Fang; Tayo, Bamidele O; Wuttke, Matthias; et al. (Kidney Int, 2022)
Estimated glomerular filtration rate (eGFR) reflects kidney function. Progressive eGFR-decline can lead to kidney failure, necessitating dialysis or transplantation. Hundreds of loci from genome-wide association studies (GWAS) for eGFR help explain population cross section variability. Since the contribution of these or other loci to eGFR-decline remains largely unknown, we derived GWAS for annual eGFR-decline and meta-analyzed 62 longitudinal studies with eGFR assessed twice over time in all 343,339 individuals and in high-risk groups. We also explored different covariate adjustment. Twelve genome-wide significant independent variants for eGFR-decline unadjusted or adjusted for eGFR-baseline (11 novel, one known for this phenotype), including nine variants robustly associated across models were identified. All loci for eGFR-decline were known for cross-sectional eGFR and thus distinguished a subgroup of eGFR loci. Seven of the nine variants showed variant-by-age interaction on eGFR cross section (further about 350,000 individuals), which linked genetic associations for eGFR-decline with age-dependency of genetic cross-section associations. Clinically important were two to four-fold greater genetic effects on eGFR-decline in high-risk subgroups. Five variants associated also with chronic kidney disease progression mapped to genes with functional in-silico evidence (UMOD, SPATA7, GALNTL5, TPPP). An unfavorable versus favorable nine-variant genetic profile showed increased risk odds ratios of 1.35 for kidney failure (95% confidence intervals 1.03-1.77) and 1.27 for acute kidney injury (95% confidence intervals 1.08-1.50) in over 2000 cases each, with matched controls). Thus, we provide a large data resource, genetic loci, and prioritized genes for kidney function decline, which help inform drug development pipelines revealing important insights into the age-dependency of kidney function genetics.

Genome Wide Association Studies of Variant-by-Thiazide Interaction on Lipids Identifies a Novel Low-Density Lipoprotein Cholesterol Locus. - Downie, Carolina G; Highland, Heather M; Lee, Moa P; Raffield, Laura M; Preuss, Michael; Whitsel, Eric A; Psaty, Bruce M; Sitlani, Colleen M; Graff, Mariaelisa; Avery, Christy L (Circ Res, 2022)
Keywords: Cholesterol, HDL; Cholesterol, LDL; Diuretics; Genome-Wide Association Study; Sodium Chloride Symporter Inhibitors; Thiazides; Triglycerides

{Genome-wide analysis of mitochondrial DNA copy number reveals loci implicated in nucleotide metabolism, platelet activation, and megakaryocyte proliferation - Longchamps, R. J.; Yang, S. Y.; Castellani, C. A.; Shi, W.; Lane, J.; Grove, M. L.; Bartz, T. M.; Sarnowski, C.; Liu, C.; Burrows, K.; Guyatt, A. L.; Gaunt, T. R.; et al. (Hum Genet, 2022)
).

Genome-wide meta-analyses reveal novel loci for verbal short-term memory and learning. - Lahti, Jari; Tuominen, Samuli; Yang, Qiong; Pergola, Giulio; Ahmad, Shahzad; Amin, Najaf; Armstrong, Nicola J; Beiser, Alexa; Bey, Katharina; Bis, Joshua C; Boerwinkle, Eric; Bressler, Jan; et al. (Mol Psychiatry, 2022)
Understanding the genomic basis of memory processes may help in combating neurodegenerative disorders. Hence, we examined the associations of common genetic variants with verbal short-term memory and verbal learning in adults without dementia or stroke (N = 53,637). We identified novel loci in the intronic region of CDH18, and at 13q21 and 3p21.1, as well as an expected signal in the APOE/APOC1/TOMM40 region. These results replicated in an independent sample. Functional and bioinformatic analyses supported many of these loci and further implicated POC1. We showed that polygenic score for verbal learning associated with brain activation in right parieto-occipital region during working memory task. Finally, we showed genetic correlations of these memory traits with several neurocognitive and health outcomes. Our findings suggest a role of several genomic loci in verbal memory processes.

{Genome-wide studies reveal factors associated with circulating uromodulin and its relationships to complex diseases - Li, Y.; Cheng, Y.; Consolato, F.; Schiano, G.; Chong, M. R.; Pietzner, M.; Nguyen, N. Q. H.; Scherer, N.; Biggs, M. L.; Kleber, M. E.; Haug, S.; Göçmen, B.; et al. (JCI Insight, 2022)
Uromodulin (UMOD) is a major risk gene for monogenic and complex forms of kidney disease. The encoded kidney-specific protein uromodulin is highly abundant in urine and related to chronic kidney disease, hypertension, and pathogen defense. To gain insights into potential systemic roles, we performed genome-wide screens of circulating uromodulin using complementary antibody-based and aptamer-based assays. We detected 3 and 10 distinct significant loci, respectively. Integration of antibody-based results at the UMOD locus with functional genomics data (RNA-Seq, ATAC-Seq, Hi-C) of primary human kidney tissue highlighted an upstream variant with differential accessibility and transcription in uromodulin-synthesizing kidney cells as underlying the observed cis effect. Shared association patterns with complex traits, including chronic kidney disease and blood pressure, placed the PRKAG2 locus in the same pathway as UMOD. Experimental validation of the third antibody-based locus, B4GALNT2, showed that the p.Cys466Arg variant of the encoded N-acetylgalactosaminyltransferase had a loss-of-function effect leading to higher serum uromodulin levels. Aptamer-based results pointed to enzymes writing glycan marks present on uromodulin and to their receptors in the circulation, suggesting that this assay permits investigating uromodulin's complex glycosylation rather than its quantitative levels. Overall, our study provides insights into circulating uromodulin and its emerging functions.

{Implicating genes, pleiotropy, and sexual dimorphism at blood lipid loci through multi-ancestry meta-analysis - Kanoni, S.; Graham, S. E.; Wang, Y.; Surakka, I.; Ramdas, S.; Zhu, X.; Clarke, S. L.; Bhatti, K. F.; Vedantam, S.; Winkler, T. W.; Locke, A. E.; Marouli, E.; et al. (Genome Biol, 2022)
Genetic variants within nearly 1000 loci are known to contribute to modulation of blood lipid levels. However, the biological pathways underlying these associations are frequently unknown, limiting understanding of these findings and hindering downstream translational efforts such as drug target discovery.\ 1,654,960) of blood lipids to prioritize putative causal genes for 2286 lipid associations using six gene prediction approaches. Using phenome-wide association (PheWAS) scans, we identify relationships of genetically predicted lipid levels to other diseases and conditions. We confirm known pleiotropic associations with cardiovascular phenotypes and determine novel associations, notably with cholelithiasis risk. We perform sex-stratified GWAS meta-analysis of lipid levels and show that 3-5% of autosomal lipid-associated loci demonstrate sex-biased effects. Finally, we report 21 novel lipid loci identified on the X chromosome. Many of the sex-biased autosomal and X chromosome lipid loci show pleiotropic associations with sex hormones, emphasizing the role of hormone regulation in lipid metabolism.\ Taken together, our findings provide insights into the biological mechanisms through which associated variants lead to altered lipid levels and potentially cardiovascular disease risk.

Insights From a Large-Scale Whole-Genome Sequencing Study of Systolic Blood Pressure, Diastolic Blood Pressure, and Hypertension. - Kelly, Tanika N; Sun, Xiao; He, Karen Y; Brown, Michael R; Taliun, Sarah A Gagliano; Hellwege, Jacklyn N; Irvin, Marguerite R; Mi, Xuenan; Brody, Jennifer A; Franceschini, Nora; Guo, Xiuqing; Hwang, Shih-Jen; et al. (Hypertension, 2022)
BACKGROUND: The availability of whole-genome sequencing data in large studies has enabled the assessment of coding and noncoding variants across the allele frequency spectrum for their associations with blood pressure. METHODS: We conducted a multiancestry whole-genome sequencing analysis of blood pressure among 51 456 Trans-Omics for Precision Medicine and Centers for Common Disease Genomics program participants (stage-1). Stage-2 analyses leveraged array data from UK Biobank (N=383 145), Million Veteran Program (N=318 891), and Reasons for Geographic and Racial Differences in Stroke (N=10 643) participants, along with whole-exome sequencing data from UK Biobank (N=199 631) participants. RESULTS: Two blood pressure signals achieved genome-wide significance in meta-analyses of stage-1 and stage-2 single variant findings (<5×10). Among them, a rare intergenic variant at novel locus, , was associated with lower systolic blood pressure in stage-1 (beta [SE]=-32.6 [6.0]; =4.99×10) but not stage-2 analysis (=0.11). Furthermore, a novel common variant at the known locus was suggestively associated with diastolic blood pressure in stage-1 (beta [SE]=-0.36 [0.07]; =4.18×10) and attained genome-wide significance in stage-2 (beta [SE]=-0.29 [0.03]; =7.28×10). Nineteen additional signals suggestively associated with blood pressure in meta-analysis of single and aggregate rare variant findings (<1×10 and <1×10, respectively). DISCUSSION: We report one promising but unconfirmed rare variant for blood pressure and, more importantly, contribute insights for future blood pressure sequencing studies. Our findings suggest promise of aggregate analyses to complement single variant analysis strategies and the need for larger, diverse samples, and family studies to enable robust rare variant identification.

Integrative analysis of clinical and epigenetic biomarkers of mortality. - Huan, Tianxiao; Nguyen, Steve; Colicino, Elena; Ochoa-Rosales, Carolina; Hill, W David; Brody, Jennifer A; Soerensen, Mette; Zhang, Yan; Baldassari, Antoine; Elhadad, Mohamed Ahmed; Toshiko, Tanaka; Zheng, Yinan; et al. (Aging Cell, 2022)
DNA methylation (DNAm) has been reported to be associated with many diseases and with mortality. We hypothesized that the integration of DNAm with clinical risk factors would improve mortality prediction. We performed an epigenome-wide association study of whole blood DNAm in relation to mortality in 15 cohorts (n = 15,013). During a mean follow-up of 10 years, there were 4314 deaths from all causes including 1235 cardiovascular disease (CVD) deaths and 868 cancer deaths. Ancestry-stratified meta-analysis of all-cause mortality identified 163 CpGs in European ancestry (EA) and 17 in African ancestry (AA) participants at p < 1 × 10 , of which 41 (EA) and 16 (AA) were also associated with CVD death, and 15 (EA) and 9 (AA) with cancer death. We built DNAm-based prediction models for all-cause mortality that predicted mortality risk after adjusting for clinical risk factors. The mortality prediction model trained by integrating DNAm with clinical risk factors showed an improvement in prediction of cancer death with 5% increase in the C-index in a replication cohort, compared with the model including clinical risk factors alone. Mendelian randomization identified 15 putatively causal CpGs in relation to longevity, CVD, or cancer risk. For example, cg06885782 (in KCNQ4) was positively associated with risk for prostate cancer (Beta = 1.2, P  = 4.1 × 10 ) and negatively associated with longevity (Beta = -1.9, P  = 0.02). Pathway analysis revealed that genes associated with mortality-related CpGs are enriched for immune- and cancer-related pathways. We identified replicable DNAm signatures of mortality and demonstrated the potential utility of CpGs as informative biomarkers for prediction of mortality risk.
Keywords: Biomarkers; Cardiovascular Diseases; DNA Methylation; Epigenesis, Genetic; Epigenomics; Humans; Male; Neoplasms

Large-scale genome-wide association study of coronary artery disease in genetically diverse populations. - Tcheandjieu, Catherine; Zhu, Xiang; Hilliard, Austin T; Clarke, Shoa L; Napolioni, Valerio; Ma, Shining; Lee, Kyung Min; Fang, Huaying; Chen, Fei; Lu, Yingchang; Tsao, Noah L; Raghavan, Sridharan; et al. (Nat Med, 2022)
We report a genome-wide association study (GWAS) of coronary artery disease (CAD) incorporating nearly a quarter of a million cases, in which existing studies are integrated with data from cohorts of white, Black and Hispanic individuals from the Million Veteran Program. We document near equivalent heritability of CAD across multiple ancestral groups, identify 95 novel loci, including nine on the X chromosome, detect eight loci of genome-wide significance in Black and Hispanic individuals, and demonstrate that two common haplotypes at the 9p21 locus are responsible for risk stratification in all populations except those of African origin, in which these haplotypes are virtually absent. Moreover, in the largest GWAS for angiographically derived coronary atherosclerosis performed to date, we find 15 loci of genome-wide significance that robustly overlap with established loci for clinical CAD. Phenome-wide association analyses of novel loci and polygenic risk scores (PRSs) augment signals related to insulin resistance, extend pleiotropic associations of these loci to include smoking and family history, and precisely document the markedly reduced transferability of existing PRSs to Black individuals. Downstream integrative analyses reinforce the critical roles of vascular endothelial, fibroblast, and smooth muscle cells in CAD susceptibility, but also point to a shared biology between atherosclerosis and oncogenesis. This study highlights the value of diverse populations in further characterizing the genetic architecture of CAD.
Keywords: Coronary Artery Disease; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Polymorphism, Single Nucleotide; Risk Factors

Longitudinal Associations of Plasma TMAO and Related Metabolites with Cognitive Impairment and Dementia in Older Adults: The Cardiovascular Health Study. - de Oliveira Otto, Marcia C; Li, Xinmin S; Wang, Zeneng; Siscovick, David; Newman, Anne B; Lai, Heidi Tsz Mung; Nemet, Ina; Lee, Yujin; Wang, Meng; Fretts, Amanda; Lemaitre, Rozenn N; Tang, W H Wilson; et al. (J Alzheimers Dis, 2022)
BACKGROUND: Animal studies suggest that gut microbiome metabolites such as trimethylamine N-oxide (TMAO) may influence cognitive function and dementia risk. However potential health effects of TMAO and related metabolites remain unclear. OBJECTIVE: We examined prospective associations of TMAO, γ-butyrobetaine, crotonobetaine, carnitine, choline, and betaine with risk of cognitive impairment and dementia among older adults aged 65 years and older in the Cardiovascular Health Study (CHS). METHODS: TMAO and metabolites were measured in stored plasma specimens collected at baseline. Incident cognitive impairment was assessed using the 100-point Modified Mini-Mental State Examination administered serially up to 7 times. Clinical dementia was identified using neuropsychological tests adjudicated by CHS Cognition Study investigators, and by ICD-9 codes from linked Medicare data. Associations of each metabolite with cognitive outcomes were assessed using Cox proportional hazards models. RESULTS: Over a median of 13 years of follow-up, 529 cases of cognitive impairment, and 522 of dementia were identified. After multivariable adjustment for relevant risk factors, no associations were seen with TMAO, carnitine, choline, or betaine. In contrast, higher crotonobetaine was associated with 20-32% higher risk of cognitive impairment and dementia per interquintile range (IQR), while γ-butyrobetaine was associated with ∼25% lower risk of the same cognitive outcomes per IQR.∥Conclusion:These findings suggest that γ-butyrobetaine, crotonobetaine, two gut microbe and host metabolites, are associated with risk of cognitive impairment and dementia. Our results indicate a need for mechanistic studies evaluating potential effects of these metabolites, and their interconversion on brain health, especially later in life.

Lung function impairment and risk of incident heart failure: the NHLBI Pooled Cohorts Study. - Eckhardt, Christina M; Balte, Pallavi P; Barr, Robert Graham; Bertoni, Alain G; Bhatt, Surya P; Cuttica, Michael; Cassano, Patricia A; Chaves, Paolo; Couper, David; Jacobs, David R; Kalhan, Ravi; Kronmal, Richard; et al. (Eur Heart J, 2022)
AIMS: The aim is to evaluate associations of lung function impairment with risk of incident heart failure (HF). METHODS AND RESULTS: Data were pooled across eight US population-based cohorts that enrolled participants from 1987 to 2004. Participants with self-reported baseline cardiovascular disease were excluded. Spirometry was used to define obstructive [forced expiratory volume in 1 s/forced vital capacity (FEV1/FVC) <0.70] or restrictive (FEV1/FVC ≥0.70, FVC <80%) lung physiology. The incident HF was defined as hospitalization or death caused by HF. In a sub-set, HF events were sub-classified as HF with reduced ejection fraction (HFrEF; EF <50%) or preserved EF (HFpEF; EF ≥50%). The Fine-Gray proportional sub-distribution hazards models were adjusted for sociodemographic factors, smoking, and cardiovascular risk factors. In models of incident HF sub-types, HFrEF, HFpEF, and non-HF mortality were treated as competing risks. Among 31 677 adults, there were 3344 incident HF events over a median follow-up of 21.0 years. Of 2066 classifiable HF events, 1030 were classified as HFrEF and 1036 as HFpEF. Obstructive [adjusted hazard ratio (HR) 1.17, 95% confidence interval (CI) 1.07-1.27] and restrictive physiology (adjusted HR 1.43, 95% CI 1.27-1.62) were associated with incident HF. Obstructive and restrictive ventilatory defects were associated with HFpEF but not HFrEF. The magnitude of the association between restrictive physiology and HFpEF was similar to associations with hypertension, diabetes, and smoking. CONCLUSION: Lung function impairment was associated with increased risk of incident HF, and particularly incident HFpEF, independent of and to a similar extent as major known cardiovascular risk factors.
Keywords: Adult; Heart Failure; Hospitalization; Humans; Lung; National Heart, Lung, and Blood Institute (U.S.); Prognosis; Risk Factors; Stroke Volume; United States

Monogenic and Polygenic Contributions to QTc Prolongation in the Population. - Nauffal, Victor; Morrill, Valerie N; Jurgens, Sean J; Choi, Seung Hoan; Hall, Amelia W; Weng, Lu-Chen; Halford, Jennifer L; Austin-Tse, Christina; Haggerty, Christopher M; Harris, Stephanie L; Wong, Eugene K; Alonso, Alvaro; et al. (Circulation, 2022)
Rare sequence variation in genes underlying cardiac repolarization and common polygenic variation influence QT interval duration. However, current clinical genetic testing of individuals with unexplained QT prolongation is restricted to examination of monogenic rare variants. The recent emergence of large-scale biorepositories with sequence data enables examination of the joint contribution of rare and common variation to the QT interval in the population. We performed a genome wide association study (GWAS) of the QTc in 84,630 United Kingdom Biobank (UKB) participants and created a polygenic risk score (PRS). Among 26,976 participants with whole genome sequencing and electrocardiogram data in the Trans-Omics for Precision Medicine (TOPMed) program, we identified 160 carriers of putative pathogenic rare variants in 10 genes known to be associated with the QT interval. We examined QTc associations with the PRS and with rare variants in TOPMed. Fifty-four independent loci were identified by GWAS in the UKB. Twenty-one loci were novel, of which 12 were replicated in TOPMed. The PRS comprising 1,110,494 common variants was significantly associated with the QTc in TOPMed (ΔQTc/ = 1.4 ms, 95% CI 1.3 -1.5; p-value=1.1×10). Carriers of putative pathogenic rare variants had longer QTc than non-carriers (ΔQTc=10.9 ms [7.4-14.4]). 23.7% of individuals with QTc>480 ms carried either a monogenic rare variant or had a PRS in the top decile (3.4% monogenic, 21% top decile of PRS). QTc duration in the population is influenced by both rare variants in genes underlying cardiac repolarization and polygenic risk, with a sizeable contribution from polygenic risk. Comprehensive assessment of the genetic determinants of QTc prolongation includes incorporation of both polygenic and monogenic risk.

Multi-ancestry genetic study of type 2 diabetes highlights the power of diverse populations for discovery and translation. - Mahajan, Anubha; Spracklen, Cassandra N; Zhang, Weihua; Ng, Maggie C Y; Petty, Lauren E; Kitajima, Hidetoshi; Yu, Grace Z; Rüeger, Sina; Speidel, Leo; Kim, Young Jin; Horikoshi, Momoko; Mercader, Josep M; et al. (Nat Genet, 2022)
We assembled an ancestrally diverse collection of genome-wide association studies (GWAS) of type 2 diabetes (T2D) in 180,834 affected individuals and 1,159,055 controls (48.9% non-European descent) through the Diabetes Meta-Analysis of Trans-Ethnic association studies (DIAMANTE) Consortium. Multi-ancestry GWAS meta-analysis identified 237 loci attaining stringent genome-wide significance (P < 5 × 10), which were delineated to 338 distinct association signals. Fine-mapping of these signals was enhanced by the increased sample size and expanded population diversity of the multi-ancestry meta-analysis, which localized 54.4% of T2D associations to a single variant with >50% posterior probability. This improved fine-mapping enabled systematic assessment of candidate causal genes and molecular mechanisms through which T2D associations are mediated, laying the foundations for functional investigations. Multi-ancestry genetic risk scores enhanced transferability of T2D prediction across diverse populations. Our study provides a step toward more effective clinical translation of T2D GWAS to improve global health for all, irrespective of genetic background.
Keywords: Diabetes Mellitus, Type 2; Ethnicity; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Polymorphism, Single Nucleotide; Risk Factors

A multi-ethnic polygenic risk score is associated with hypertension prevalence and progression throughout adulthood. - Kurniansyah, Nuzulul; Goodman, Matthew O; Kelly, Tanika N; Elfassy, Tali; Wiggins, Kerri L; Bis, Joshua C; Guo, Xiuqing; Palmas, Walter; Taylor, Kent D; Lin, Henry J; Haessler, Jeffrey; Gao, Yan; et al. (Nat Commun, 2022)
In a multi-stage analysis of 52,436 individuals aged 17-90 across diverse cohorts and biobanks, we train, test, and evaluate a polygenic risk score (PRS) for hypertension risk and progression. The PRS is trained using genome-wide association studies (GWAS) for systolic, diastolic blood pressure, and hypertension, respectively. For each trait, PRS is selected by optimizing the coefficient of variation (CV) across estimated effect sizes from multiple potential PRS using the same GWAS, after which the 3 trait-specific PRSs are combined via an unweighted sum called "PRSsum", forming the HTN-PRS. The HTN-PRS is associated with both prevalent and incident hypertension at 4-6 years of follow up. This association is further confirmed in age-stratified analysis. In an independent biobank of 40,201 individuals, the HTN-PRS is confirmed to be predictive of increased risk for coronary artery disease, ischemic stroke, type 2 diabetes, and chronic kidney disease.
Keywords: Adult; Diabetes Mellitus, Type 2; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Hypertension; Multifactorial Inheritance; Prevalence; Risk Factors

Multi-Scalar Data Integration Links Glomerular Angiopoietin-Tie Signaling Pathway Activation With Progression of Diabetic Kidney Disease. - Liu, Jiahao; Nair, Viji; Zhao, Yi-Yang; Chang, Dong-Yuan; Limonte, Christine; Bansal, Nisha; Fermin, Damian; Eichinger, Felix; Tanner, Emily C; Bellovich, Keith A; Steigerwalt, Susan; Bhat, Zeenat; et al. (Diabetes, 2022)
Diabetic kidney disease (DKD) is the leading cause of end-stage kidney disease (ESKD). Prognostic biomarkers reflective of underlying molecular mechanisms are critically needed for effective management of DKD. A three-marker panel was derived from a proteomics analysis of plasma samples by an unbiased machine learning approach from participants (N = 58) in the Clinical Phenotyping and Resource Biobank study. In combination with standard clinical parameters, this panel improved prediction of the composite outcome of ESKD or a 40% decline in glomerular filtration rate. The panel was validated in an independent group (N = 68), who also had kidney transcriptomic profiles. One marker, plasma angiopoietin 2 (ANGPT2), was significantly associated with outcomes in cohorts from the Cardiovascular Health Study (N = 3,183) and the Chinese Cohort Study of Chronic Kidney Disease (N = 210). Glomerular transcriptional angiopoietin/Tie (ANG-TIE) pathway scores, derived from the expression of 154 ANG-TIE signaling mediators, correlated positively with plasma ANGPT2 levels and kidney outcomes. Higher receptor expression in glomeruli and higher ANG-TIE pathway scores in endothelial cells corroborated potential functional effects in the kidney from elevated plasma ANGPT2 levels. Our work suggests that ANGPT2 is a promising prognostic endothelial biomarker with likely functional impact on glomerular pathogenesis in DKD.
Keywords: Angiopoietin-1; Angiopoietin-2; Angiopoietins; Biomarkers; Cohort Studies; Diabetes Mellitus; Diabetic Nephropathies; Disease Progression; Endothelial Cells; Humans; Kidney Failure, Chronic; Receptor, TIE-2; Signal Transduction

New insights into the genetic etiology of Alzheimer's disease and related dementias. - Bellenguez, Céline; Küçükali, Fahri; Jansen, Iris E; Kleineidam, Luca; Moreno-Grau, Sonia; Amin, Najaf; Naj, Adam C; Campos-Martin, Rafael; Grenier-Boley, Benjamin; Andrade, Victor; Holmans, Peter A; Boland, Anne; et al. (Nat Genet, 2022)
Characterization of the genetic landscape of Alzheimer's disease (AD) and related dementias (ADD) provides a unique opportunity for a better understanding of the associated pathophysiological processes. We performed a two-stage genome-wide association study totaling 111,326 clinically diagnosed/'proxy' AD cases and 677,663 controls. We found 75 risk loci, of which 42 were new at the time of analysis. Pathway enrichment analyses confirmed the involvement of amyloid/tau pathways and highlighted microglia implication. Gene prioritization in the new loci identified 31 genes that were suggestive of new genetically associated processes, including the tumor necrosis factor alpha pathway through the linear ubiquitin chain assembly complex. We also built a new genetic risk score associated with the risk of future AD/dementia or progression from mild cognitive impairment to AD/dementia. The improvement in prediction led to a 1.6- to 1.9-fold increase in AD risk from the lowest to the highest decile, in addition to effects of age and the APOE ε4 allele.
Keywords: Alzheimer Disease; Cognitive Dysfunction; Genome-Wide Association Study; Humans; tau Proteins

{Obesity Partially Mediates the Diabetogenic Effect of Lowering LDL Cholesterol - Wu, P.; Moon, J. Y.; Daghlas, I.; Franco, G.; Porneala, B. C.; Ahmadizar, F.; Richardson, T. G.; Isaksen, J. L.; Hindy, G.; Yao, J.; Sitlani, C. M.; Raffield, L. M.; et al. (Diabetes Care, 2022)
LDL cholesterol (LDLc)-lowering drugs modestly increase body weight and type 2 diabetes risk, but the extent to which the diabetogenic effect of lowering LDLc is mediated through increased BMI is unknown.\ We conducted summary-level univariable and multivariable Mendelian randomization (MR) analyses in 921,908 participants to investigate the effect of lowering LDLc on type 2 diabetes risk and the proportion of this effect mediated through BMI. We used data from 92,532 participants from 14 observational studies to replicate findings in individual-level MR analyses.\ A 1-SD decrease in genetically predicted LDLc was associated with increased type 2 diabetes odds (odds ratio [OR] 1.12 [95% CI 1.01, 1.24]) and BMI (β = 0.07 SD units [95% CI 0.02, 0.12]) in univariable MR analyses. The multivariable MR analysis showed evidence of an indirect effect of lowering LDLc on type 2 diabetes through BMI (OR 1.04 [95% CI 1.01, 1.08]) with a proportion mediated of 38% of the total effect (P = 0.03). Total and indirect effect estimates were similar across a number of sensitivity analyses. Individual-level MR analyses confirmed the indirect effect of lowering LDLc on type 2 diabetes through BMI with an estimated proportion mediated of 8% (P = 0.04).\ These findings suggest that the diabetogenic effect attributed to lowering LDLc is partially mediated through increased BMI. Our results could help advance understanding of adipose tissue and lipids in type 2 diabetes pathophysiology and inform strategies to reduce diabetes risk among individuals taking LDLc-lowering medications.

Plasma proteomic signature of decline in gait speed and grip strength. - Liu, Xiaojuan; Pan, Stephanie; Xanthakis, Vanessa; Vasan, Ramachandran S; Psaty, Bruce M; Austin, Thomas R; Newman, Anne B; Sanders, Jason L; Wu, Chenkai; Tracy, Russell P; Gerszten, Robert E; Odden, Michelle C (Aging Cell, 2022)
The biological mechanisms underlying decline in physical function with age remain unclear. We examined the plasma proteomic profile associated with longitudinal changes in physical function measured by gait speed and grip strength in community-dwelling adults. We applied an aptamer-based platform to assay 1154 plasma proteins on 2854 participants (60% women, aged 76 years) in the Cardiovascular Health Study (CHS) in 1992-1993 and 1130 participants (55% women, aged 54 years) in the Framingham Offspring Study (FOS) in 1991-1995. Gait speed and grip strength were measured annually for 7 years in CHS and at cycles 7 (1998-2001) and 8 (2005-2008) in FOS. The associations of individual protein levels (log-transformed and standardized) with longitudinal changes in gait speed and grip strength in two populations were examined separately by linear mixed-effects models. Meta-analyses were implemented using random-effects models and corrected for multiple testing. We found that plasma levels of 14 and 18 proteins were associated with changes in gait speed and grip strength, respectively (corrected p < 0.05). The proteins most strongly associated with gait speed decline were GDF-15 (Meta-analytic p = 1.58 × 10 ), pleiotrophin (1.23 × 10 ), and TIMP-1 (5.97 × 10 ). For grip strength decline, the strongest associations were for carbonic anhydrase III (1.09 × 10 ), CDON (2.38 × 10 ), and SMOC1 (7.47 × 10 ). Several statistically significant proteins are involved in the inflammatory responses or antagonism of activin by follistatin pathway. These novel proteomic biomarkers and pathways should be further explored as future mechanisms and targets for age-related functional decline.
Keywords: Adult; Female; Gait; Hand Strength; Humans; Independent Living; Male; Proteomics; Walking Speed

Polygenic transcriptome risk scores for COPD and lung function improve cross-ethnic portability of prediction in the NHLBI TOPMed program. - Hu, Xiaowei; Qiao, Dandi; Kim, Wonji; Moll, Matthew; Balte, Pallavi P; Lange, Leslie A; Bartz, Traci M; Kumar, Rajesh; Li, Xingnan; Yu, Bing; Cade, Brian E; Laurie, Cecelia A; et al. (Am J Hum Genet, 2022)
While polygenic risk scores (PRSs) enable early identification of genetic risk for chronic obstructive pulmonary disease (COPD), predictive performance is limited when the discovery and target populations are not well matched. Hypothesizing that the biological mechanisms of disease are shared across ancestry groups, we introduce a PrediXcan-derived polygenic transcriptome risk score (PTRS) to improve cross-ethnic portability of risk prediction. We constructed the PTRS using summary statistics from application of PrediXcan on large-scale GWASs of lung function (forced expiratory volume in 1 s [FEV] and its ratio to forced vital capacity [FEV/FVC]) in the UK Biobank. We examined prediction performance and cross-ethnic portability of PTRS through smoking-stratified analyses both on 29,381 multi-ethnic participants from TOPMed population/family-based cohorts and on 11,771 multi-ethnic participants from TOPMed COPD-enriched studies. Analyses were carried out for two dichotomous COPD traits (moderate-to-severe and severe COPD) and two quantitative lung function traits (FEV and FEV/FVC). While the proposed PTRS showed weaker associations with disease than PRS for European ancestry, the PTRS showed stronger association with COPD than PRS for African Americans (e.g., odds ratio [OR] = 1.24 [95% confidence interval [CI]: 1.08-1.43] for PTRS versus 1.10 [0.96-1.26] for PRS among heavy smokers with ≥ 40 pack-years of smoking) for moderate-to-severe COPD. Cross-ethnic portability of the PTRS was significantly higher than the PRS (paired t test p < 2.2 × 10 with portability gains ranging from 5% to 28%) for both dichotomous COPD traits and across all smoking strata. Our study demonstrates the value of PTRS for improved cross-ethnic portability compared to PRS in predicting COPD risk.

Pooled Cohort Probability Score for Subclinical Airflow Obstruction. - Bhatt, Surya P; Balte, Pallavi P; Schwartz, Joseph E; Jaeger, Byron C; Cassano, Patricia A; Chaves, Paulo H; Couper, David; Jacobs, David R; Kalhan, Ravi; Kaplan, Robert; Lloyd-Jones, Donald; Newman, Anne B; et al. (Ann Am Thorac Soc, 2022)
Early detection of chronic obstructive pulmonary disease (COPD) is a public health priority. Airflow obstruction is the single most important risk factor for adverse COPD outcomes, but spirometry is not routinely recommended for screening. To describe the burden of subclinical airflow obstruction (SAO) and to develop a probability score for SAO to inform potential detection and prevention programs. Lung function and clinical data were harmonized and pooled across nine U.S. general population cohorts. Adults with respiratory symptoms, inhaler use, or prior diagnosis of COPD or asthma were excluded. A probability score for prevalent SAO (forced expiratory volume in 1 second/forced vital capacity < 0.70) was developed via hierarchical group-lasso regularization from clinical variables in strata of sex and smoking status, and its discriminative accuracy for SAO was assessed in the pooled cohort as well as in an external validation cohort (NHANES [National Health and Nutrition Examination Survey] 2011-2012). Incident hospitalizations and deaths due to COPD (respiratory events) were defined by adjudication or administrative criteria in four of nine cohorts. Of 33,546 participants (mean age 52 yr, 54% female, 44% non-Hispanic White), 4,424 (13.2%) had prevalent SAO. The incidence of respiratory events ( = 14,024) was threefold higher in participants with SAO versus those without (152 vs. 39 events/10,000 person-years). The probability score, which was based on six commonly available variables (age, sex, race and/or ethnicity, body mass index, smoking status, and smoking pack-years) was well calibrated and showed excellent discrimination in both the testing sample (C-statistic, 0.81; 95% confidence interval [CI], 0.80-0.82) and in NHANES (C-statistic, 0.83; 95% CI, 0.80-0.86). Among participants with predicted probabilities ⩾ 15%, 3.2 would need to undergo spirometry to detect one case of SAO. Adults with SAO demonstrate excess respiratory hospitalization and mortality. A probability score for SAO using commonly available clinical risk factors may be suitable for targeting screening and primary prevention strategies.
Keywords: Adult; Female; Forced Expiratory Volume; Humans; Lung; Male; Middle Aged; Nutrition Surveys; Pulmonary Disease, Chronic Obstructive; Risk Factors; Spirometry; Vital Capacity

{A population-based meta-analysis of circulating GFAP for cognition and dementia risk - Gonzales, M. M.; Wiedner, C.; Wang, C. P.; Liu, Q.; Bis, J. C.; Li, Z.; Himali, J. J.; Ghosh, S.; Thomas, E. A.; Parent, D. M.; Kautz, T. F.; Pase, M. P.; et al. (Ann Clin Transl Neurol, 2022)
Expression of glial fibrillary acidic protein (GFAP), a marker of reactive astrocytosis, colocalizes with neuropathology in the brain. Blood levels of GFAP have been associated with cognitive decline and dementia status. However, further examinations at a population-based level are necessary to broaden generalizability to community settings.\ Circulating GFAP levels were assayed using a Simoa HD-1 analyzer in 4338 adults without prevalent dementia from four longitudinal community-based cohort studies. The associations between GFAP levels with general cognition, total brain volume, and hippocampal volume were evaluated with separate linear regression models in each cohort with adjustment for age, sex, education, race, diabetes, systolic blood pressure, antihypertensive medication, body mass index, apolipoprotein E ε4 status, site, and time between GFAP blood draw and the outcome. Associations with incident all-cause and Alzheimer's disease dementia were evaluated with adjusted Cox proportional hazard models. Meta-analysis was performed on the estimates derived from each cohort using random-effects models.\ 0.05). However, each standard deviation unit increase in log-transformed GFAP levels was significantly associated with a 2.5-fold higher risk of incident all-cause dementia (Hazard Ratio [HR]: 2.47 (95% CI: 1.52-4.01)) and Alzheimer's disease dementia (HR: 2.54 [95% CI: 1.42-4.53]) over up to 15-years of follow-up.\ Results support the potential role of circulating GFAP levels for aiding dementia risk prediction and improving clinical trial stratification in community settings.

Proteomics and Population Biology in the Cardiovascular Health Study (CHS): design of a study with mentored access and active data sharing. - Austin, Thomas R; McHugh, Caitlin P; Brody, Jennifer A; Bis, Joshua C; Sitlani, Colleen M; Bartz, Traci M; Biggs, Mary L; Bansal, Nisha; Bůzková, Petra; Carr, Steven A; deFilippi, Christopher R; Elkind, Mitchell S V; et al. (Eur J Epidemiol, 2022)
BACKGROUND: In the last decade, genomic studies have identified and replicated thousands of genetic associations with measures of health and disease and contributed to the understanding of the etiology of a variety of health conditions. Proteins are key biomarkers in clinical medicine and often drug-therapy targets. Like genomics, proteomics can advance our understanding of biology. METHODS AND RESULTS: In the setting of the Cardiovascular Health Study (CHS), a cohort study of older adults, an aptamer-based method that has high sensitivity for low-abundance proteins was used to assay 4979 proteins in frozen, stored plasma from 3188 participants (61% women, mean age 74 years). CHS provides active support, including central analysis, for seven phenotype-specific working groups (WGs). Each CHS WG is led by one or two senior investigators and includes 10 to 20 early or mid-career scientists. In this setting of mentored access, the proteomic data and analytic methods are widely shared with the WGs and investigators so that they may evaluate associations between baseline levels of circulating proteins and the incidence of a variety of health outcomes in prospective cohort analyses. We describe the design of CHS, the CHS Proteomics Study, characteristics of participants, quality control measures, and structural characteristics of the data provided to CHS WGs. We additionally highlight plans for validation and replication of novel proteomic associations. CONCLUSION: The CHS Proteomics Study offers an opportunity for collaborative data sharing to improve our understanding of the etiology of a variety of health conditions in older adults.

PUFA ω-3 and ω-6 biomarkers and sleep: a pooled analysis of cohort studies on behalf of the Fatty Acids and Outcomes Research Consortium (FORCE). - Murphy, Rachel A; Tintle, Nathan; Harris, William S; Darvishian, Maryam; Marklund, Matti; Virtanen, Jyrki K; Hantunen, Sari; de Mello, Vanessa D; Tuomilehto, Jaakko; Lindström, Jaana; Bolt, Matthew A; Brouwer, Ingeborg A; et al. (Am J Clin Nutr, 2022)
BACKGROUND: n-3 and n-6 PUFAs have physiologic roles in sleep processes, but little is known regarding circulating n-3 and n-6 PUFA and sleep parameters. OBJECTIVES: We sought to assess associations between biomarkers of n-3 and n-6 PUFA intake with self-reported sleep duration and difficulty falling sleeping in the Fatty Acids and Outcome Research Consortium. METHODS: Harmonized, de novo, individual-level analyses were performed and pooled across 12 cohorts. Participants were 35-96 y old and from 5 nations. Circulating measures included α-linolenic acid (ALA), EPA, docosapentaenoic acid (DPA), DHA, EPA + DPA + DHA, linoleic acid, and arachidonic acid. Sleep duration (10 cohorts, n = 18,791) was categorized as short (≤6 h), 7-8 h (reference), or long (≥9 h). Difficulty falling asleep (8 cohorts, n = 12,500) was categorized as yes or no. Associations between PUFAs, sleep duration, and difficulty falling sleeping were assessed by cross-sectional multinomial logistic regression using standardized protocols and covariates. Cohort-specific multivariable-adjusted ORs per quintile of PUFAs were pooled with inverse-variance weighted meta-analysis. RESULTS: In pooled analysis adjusted for sociodemographic characteristics and health status, participants with higher very long-chain n-3 PUFAs were less likely to have long sleep duration. In the top compared with the bottom quintiles, the multivariable-adjusted ORs (95% CIs) for long sleep were 0.78 (95% CI: 0.65, 0.95) for DHA and 0.76 (95% CI: 0.63, 0.93) for EPA + DPA + DHA. Significant associations for ALA and n-6 PUFA with short sleep duration or difficulty falling sleeping were not identified. CONCLUSIONS: Participants with higher concentrations of very long-chain n-3 PUFAs were less likely to have long sleep duration. While objective biomarkers reduce recall bias and misclassification, the cross-sectional design limits assessment of the temporal nature of this relation. These novel findings across 12 cohorts highlight the need for experimental and biological assessments of very long-chain n-3 PUFAs and sleep duration.
Keywords: Biomarkers; Cohort Studies; Cross-Sectional Studies; Fatty Acids; Fatty Acids, Omega-3; Humans; Outcome Assessment, Health Care; Sleep

Rare coding variants in 35 genes associate with circulating lipid levels-A multi-ancestry analysis of 170,000 exomes. - Hindy, George; Dornbos, Peter; Chaffin, Mark D; Liu, Dajiang J; Wang, Minxian; Selvaraj, Margaret Sunitha; Zhang, David; Park, Joseph; Aguilar-Salinas, Carlos A; Antonacci-Fulton, Lucinda; Ardissino, Diego; Arnett, Donna K; et al. (Am J Hum Genet, 2022)
Large-scale gene sequencing studies for complex traits have the potential to identify causal genes with therapeutic implications. We performed gene-based association testing of blood lipid levels with rare (minor allele frequency < 1%) predicted damaging coding variation by using sequence data from >170,000 individuals from multiple ancestries: 97,493 European, 30,025 South Asian, 16,507 African, 16,440 Hispanic/Latino, 10,420 East Asian, and 1,182 Samoan. We identified 35 genes associated with circulating lipid levels; some of these genes have not been previously associated with lipid levels when using rare coding variation from population-based samples. We prioritize 32 genes in array-based genome-wide association study (GWAS) loci based on aggregations of rare coding variants; three (EVI5, SH2B3, and PLIN1) had no prior association of rare coding variants with lipid levels. Most of our associated genes showed evidence of association among multiple ancestries. Finally, we observed an enrichment of gene-based associations for low-density lipoprotein cholesterol drug target genes and for genes closest to GWAS index single-nucleotide polymorphisms (SNPs). Our results demonstrate that gene-based associations can be beneficial for drug target development and provide evidence that the gene closest to the array-based GWAS index SNP is often the functional gene for blood lipid levels.
Keywords: Alleles; Blood Glucose; Case-Control Studies; Computational Biology; Databases, Genetic; Diabetes Mellitus, Type 2; Exome; Genetic Predisposition to Disease; Genetic Variation; Genetics, Population; Genome-Wide Association Study; Humans; Lipid Metabolism; Lipids; Liver; Molecular Sequence Annotation; Multifactorial Inheritance; Open Reading Frames; Phenotype; Polymorphism, Single Nucleotide

Rare genetic variants explain missing heritability in smoking. - Jang, Seon-Kyeong; Evans, Luke; Fialkowski, Allison; Arnett, Donna K; Ashley-Koch, Allison E; Barnes, Kathleen C; Becker, Diane M; Bis, Joshua C; Blangero, John; Bleecker, Eugene R; Boorgula, Meher Preethi; Bowden, Donald W; et al. (Nat Hum Behav, 2022)
Common genetic variants explain less variation in complex phenotypes than inferred from family-based studies, and there is a debate on the source of this 'missing heritability'. We investigated the contribution of rare genetic variants to tobacco use with whole-genome sequences from up to 26,257 unrelated individuals of European ancestries and 11,743 individuals of African ancestries. Across four smoking traits, single-nucleotide-polymorphism-based heritability ([Formula: see text]) was estimated from 0.13 to 0.28 (s.e., 0.10-0.13) in European ancestries, with 35-74% of it attributable to rare variants with minor allele frequencies between 0.01% and 1%. These heritability estimates are 1.5-4 times higher than past estimates based on common variants alone and accounted for 60% to 100% of our pedigree-based estimates of narrow-sense heritability ([Formula: see text], 0.18-0.34). In the African ancestry samples, [Formula: see text] was estimated from 0.03 to 0.33 (s.e., 0.09-0.14) across the four smoking traits. These results suggest that rare variants are important contributors to the heritability of smoking.

{Replication study of AD-associated rare variants - Neupane, A.; Lenny, B.; Budde, J. P.; Wang, F.; Norton, J.; Morris, J. C.; Cruchaga, C.; Fernández, M. V. (Alzheimers Dement, 2022)

{A saturated map of common genetic variants associated with human height - Yengo, L.; Vedantam, S.; Marouli, E.; Sidorenko, J.; Bartell, E.; Sakaue, S.; Graff, M.; Eliasen, A. U.; Jiang, Y.; Raghavan, S.; Miao, J.; Arias, J. D.; et al. (Nature, 2022)
) account for 40% (45%) of phenotypic variance in populations of European ancestry but only around 10-20% (14-24%) in populations of other ancestries. Effect sizes, associated regions and gene prioritization are similar across ancestries, indicating that reduced prediction accuracy is likely to be explained by linkage disequilibrium and differences in allele frequency within associated regions. Finally, we show that the relevant biological pathways are detectable with smaller sample sizes than are needed to implicate causal genes and variants. Overall, this study provides a comprehensive map of specific genomic regions that contain the vast majority of common height-associated variants. Although this map is saturated for populations of European ancestry, further research is needed to achieve equivalent saturation in other ancestries.

Sleep problems and risk of cancer incidence and mortality in an older cohort: The Cardiovascular Health Study (CHS). - Sillah, Arthur; Watson, Nathaniel F; Peters, Ulrike; Biggs, Mary L; Nieto, F Javier; Li, Christopher I; Gozal, David; Thornton, Timothy; Barrie, Sonnah; Phipps, Amanda I (Cancer Epidemiol, 2022)
BACKGROUND: Sleep problems (SP) can indicate underlying sleep disorders, such as obstructive sleep apnea, which may adversely impact cancer risk and mortality. METHODS: We assessed the association of baseline and longitudinal sleep apnea and insomnia symptoms with incident cancer (N = 3930) and cancer mortality (N = 4580) in the Cardiovascular Health Study. We used Cox proportional hazards regression to calculate adjusted hazard ratios (HR) and 95% confidence intervals (CI) to evaluate the associations. RESULTS: Overall, 885 incident cancers and 804 cancer deaths were identified over a median follow-up of 12 and 14 years, respectively. Compared to participants who reported no sleep apnea symptoms, the risk of incident cancer was inversely associated [(HR (95%CI)] with snoring [0.84 (0.71, 0.99)]. We noted an elevated prostate cancer incidence for apnea [2.34 (1.32, 4.15)] and snoring [1.69 (1.11, 2.57)]. We also noted an elevated HR for lymphatic or hematopoietic cancers [daytime sleepiness: 1.81 (1.06, 3.08)]. We found an inverse relationship for cancer mortality with respect to snoring [0.73 (0.62, 0.8)] and apnea [(0.69 (0.51, 0.94))]. We noted a significant inverse relationship between difficulty falling asleep and colorectal cancer death [0.32 (0.15, 0.69)] and snoring with lung cancer death [0.56 (0.35, 0.89)]. CONCLUSIONS: The relationship between SP and cancer risk and mortality was heterogeneous. Larger prospective studies addressing more cancer sites, molecular type-specific associations, and better longitudinal SP assessments are needed for improved delineation of SP-cancer risk dyad.

Stroke genetics informs drug discovery and risk prediction across ancestries. - Mishra, Aniket; Malik, Rainer; Hachiya, Tsuyoshi; Jürgenson, Tuuli; Namba, Shinichi; Posner, Daniel C; Kamanu, Frederick K; Koido, Masaru; Le Grand, Quentin; Shi, Mingyang; He, Yunye; Georgakis, Marios K; et al. (Nature, 2022)
Previous genome-wide association studies (GWASs) of stroke - the second leading cause of death worldwide - were conducted predominantly in populations of European ancestry. Here, in cross-ancestry GWAS meta-analyses of 110,182 patients who have had a stroke (five ancestries, 33% non-European) and 1,503,898 control individuals, we identify association signals for stroke and its subtypes at 89 (61 new) independent loci: 60 in primary inverse-variance-weighted analyses and 29 in secondary meta-regression and multitrait analyses. On the basis of internal cross-ancestry validation and an independent follow-up in 89,084 additional cases of stroke (30% non-European) and 1,013,843 control individuals, 87% of the primary stroke risk loci and 60% of the secondary stroke risk loci were replicated (P < 0.05). Effect sizes were highly correlated across ancestries. Cross-ancestry fine-mapping, in silico mutagenesis analysis, and transcriptome-wide and proteome-wide association analyses revealed putative causal genes (such as SH3PXD2A and FURIN) and variants (such as at GRK5 and NOS3). Using a three-pronged approach, we provide genetic evidence for putative drug effects, highlighting F11, KLKB1, PROC, GP1BA, LAMC2 and VCAM1 as possible targets, with drugs already under investigation for stroke for F11 and PROC. A polygenic score integrating cross-ancestry and ancestry-specific stroke GWASs with vascular-risk factor GWASs (integrative polygenic scores) strongly predicted ischaemic stroke in populations of European, East Asian and African ancestry. Stroke genetic risk scores were predictive of ischaemic stroke independent of clinical risk factors in 52,600 clinical-trial participants with cardiometabolic disease. Our results provide insights to inform biology, reveal potential drug targets and derive genetic risk prediction tools across ancestries.

Targeted Genome Sequencing Identifies Multiple Rare Variants in Caveolin-1 Associated with Obstructive Sleep Apnea. - Liang, Jingjing; Wang, Heming; Cade, Brian E; Kurniansyah, Nuzulul; He, Karen Y; Lee, Jiwon; Sands, Scott A; Brody, Jennifer; Chen, Han; Gottlieb, Daniel J; Evans, Daniel S; Guo, Xiuqing; et al. (Am J Respir Crit Care Med, 2022)
INTRODUCTION: Obstructive sleep apnea (OSA) is a common disorder associated with increased risk for cardiovascular disease, diabetes, and premature mortality. There is strong clinical and epi-demiologic evidence supporting the importance of genetic factors influencing OSA, but limited data implicating specific genes. METHODS: Leveraging high depth genomic sequencing data from the National Heart, Lung, and Blood Institute (NHLBI) Trans-Omics for Precision Medicine (TOPMed) program and imputed genotype data from multiple population-based studies, we performed linkage analysis in the Cleve-land Family Study (CFS) followed by multi-stage gene-based association analyses in independent cohorts to search for rare variants contributing to OSA severity as assessed by the apnea-hypopnea index (AHI) in a total of 7,708 individuals of European ancestry. RESULTS: Linkage analysis in CFS identified a suggestive linkage peak on chromosome 7q31 (LOD=2.31). Gene-based analysis identified 21 non-coding rare variants in Caveolin-1 (CAV1) associated with lower AHI after accounting for multiple comparisons (p=7.4×10-8). These non-coding variants together significantly contributed to the linkage evidence (p<10-3). Follow-up anal-ysis revealed significant associations between these variants and increased CAV1 expression, and increased CAV1 expression in peripheral monocytes was associated with lower AHI (p=0.024) and higher minimum overnight oxygen saturation (p=0.007). CONCLUSION: Rare variants in CAV1, a membrane scaffolding protein essential in multiple cellular and metabolic functions, are associated with higher CAV1 gene expression and lower OSA severity, suggesting a novel target for modulating OSA severity.

{Trans Fatty Acid Biomarkers and Incident Type 2 Diabetes: Pooled Analysis of 12 Prospective Cohort Studies in the Fatty Acids and Outcomes Research Consortium (FORCE) - Lai, H. T. M.; Imamura, F.; Korat, A. V. A.; Murphy, R. A.; Tintle, N.; Bassett, J. K.; Chen, J.; ger, J.; Chien, K. L.; Senn, M.; Wood, A. C.; Forouhi, N. G.; et al. (Diabetes Care, 2022)
Trans fatty acids (TFAs) have harmful biologic effects that could increase the risk of type 2 diabetes (T2D), but evidence remains uncertain. We aimed to investigate the prospective associations of TFA biomarkers and T2D by conducting an individual participant-level pooled analysis.\ 18 years without prevalent diabetes. Each cohort conducted de novo harmonized analyses using a prespecified protocol, and findings were pooled using inverse-variance weighted meta-analysis. Heterogeneity was explored by prespecified between-study and within-study characteristics.\ 0.1).\ Circulating individual trans-18:2 TFA biomarkers were not associated with risk of T2D, while trans-16:1n-9, total trans-18:1, and total trans-18:2 were inversely associated. Findings may reflect the influence of mixed TFA sources (industrial vs. natural ruminant), a general decline in TFA exposure due to policy changes during this period, or the relatively limited range of TFA levels.

Trimethylamine N-oxide and hip fracture and bone mineral density in older adults: The cardiovascular health study. - Elam, Rachel E; Bůzková, Petra; Barzilay, Joshua I; Wang, Zeneng; Nemet, Ina; Budoff, Matthew J; Cauley, Jane A; Fink, Howard A; Lee, Yujin; Robbins, John A; Wang, Meng; Hazen, Stanley L; et al. (Bone, 2022)
CONTEXT: Gut microbiota-derived metabolite trimethylamine N-oxide (TMAO) may adversely affect bone by inducing oxidative stress. Whether this translates into increased fracture risk in older adults is uncertain. OBJECTIVE: Determine the associations of plasma TMAO with hip fracture and bone mineral density (BMD) in older adults. DESIGN AND SETTING: Cox hazard models and linear regression stratified by sex examined the associations of TMAO with hip fracture and BMD in the longitudinal cohort of the Cardiovascular Health Study. PARTICIPANTS: 5019 U.S. adults aged ≥65 years. EXPOSURE: Plasma TMAO. MAIN OUTCOME MEASURES: Incident hip fractures; total hip BMD dual x-ray absorptiometry in a subset (n = 1400). RESULTS: Six hundred sixty-six incident hip fractures occurred during up to 26 years of follow-up (67,574 person-years). After multivariable adjustment, TMAO was not significantly associated with hip fracture (women: hazard ratio (HR) [95% confidence interval (CI)] of 1.00[0.92,1.09] per TMAO doubling; men: 1.12[0.95,1.33]). TMAO was also not associated with total hip BMD (women: BMD difference [95% CI] of 0.42 g/cm*100 [-0.34,1.17] per TMAO doubling; men: 0.19[-1.04,1.42]). In exploratory analyses, we found an interaction between body mass index (BMI) and the association of TMAO with hip fracture (P < 0.01). Higher TMAO was significantly associated with risk of hip fracture in adults with overweight or obesity (BMI ≥ 25) (HR [95% CI]:1.17[1.05,1.31]), but not normal or underweight. CONCLUSIONS: Among older US men and women, TMAO was not significantly associated with risk of hip fracture or BMD overall. Exploratory analyses suggested a significant association between higher TMAO and hip fracture when BMI was elevated, which merits further study.
Keywords: Absorptiometry, Photon; Aged; Bone Density; Female; Hip Fractures; Humans; Male; Methylamines; Risk Factors

The Value of Rare Genetic Variation in the Prediction of Common Obesity in European Ancestry Populations. - Wang, Zhe; Choi, Shing Wan; Chami, Nathalie; Boerwinkle, Eric; Fornage, Myriam; Redline, Susan; Bis, Joshua C; Brody, Jennifer A; Psaty, Bruce M; Kim, Wonji; McDonald, Merry-Lynn N; Regan, Elizabeth A; et al. (Front Endocrinol (Lausanne), 2022)
Polygenic risk scores (PRSs) aggregate the effects of genetic variants across the genome and are used to predict risk of complex diseases, such as obesity. Current PRSs only include common variants (minor allele frequency (MAF) ≥1%), whereas the contribution of rare variants in PRSs to predict disease remains unknown. Here, we examine whether augmenting the standard common variant PRS (PRS) with a rare variant PRS (PRS) improves prediction of obesity. We used genome-wide genotyped and imputed data on 451,145 European-ancestry participants of the UK Biobank, as well as whole exome sequencing (WES) data on 184,385 participants. We performed single variant analyses (for both common and rare variants) and gene-based analyses (for rare variants) for association with BMI (kg/m), obesity (BMI ≥ 30 kg/m), and extreme obesity (BMI ≥ 40 kg/m). We built PRSs and PRSs using a range of methods (Clumping+Thresholding [C+T], PRS-CS, lassosum, gene-burden test). We selected the best-performing PRSs and assessed their performance in 36,757 European-ancestry unrelated participants with whole genome sequencing (WGS) data from the Trans-Omics for Precision Medicine (TOPMed) program. The best-performing PRS explained 10.1% of variation in BMI, and 18.3% and 22.5% of the susceptibility to obesity and extreme obesity, respectively, whereas the best-performing PRS explained 1.49%, and 2.97% and 3.68%, respectively. The PRS was associated with an increased risk of obesity and extreme obesity (OR = 1.37 per SD, = 1.7x10; OR = 1.55 per SD, = 3.8x10), which was attenuated, after adjusting for PRS (OR = 1.08 per SD, = 9.8x10; OR= 1.09 per SD, = 0.02). When PRS and PRS are combined, the increase in explained variance attributed to PRS was small (incremental Nagelkerke R = 0.24% for obesity and 0.51% for extreme obesity). Consistently, combining PRS to PRS provided little improvement to the prediction of obesity (PRS AUC = 0.591; PRS AUC = 0.708; PRS AUC = 0.710). In summary, while rare variants show convincing association with BMI, obesity and extreme obesity, the PRS provides limited improvement over PRS in the prediction of obesity risk, based on these large populations.
Keywords: Gene Frequency; Genetic Variation; Genome-Wide Association Study; Humans; Obesity; Whole Genome Sequencing

Whole exome sequencing of 14 389 individuals from the ESP and CHARGE consortia identifies novel rare variation associated with hemostatic factors. - Pankratz, Nathan; Wei, Peng; Brody, Jennifer A; Chen, Ming-Huei; Vries, Paul S; Huffman, Jennifer E; Stimson, Mary Rachel; Auer, Paul L; Boerwinkle, Eric; Cushman, Mary; Maat, Moniek P M; Folsom, Aaron R; et al. (Hum Mol Genet, 2022)
Plasma levels of fibrinogen, coagulation factors VII and VIII, and von Willebrand factor (vWF) are four intermediate phenotypes that are heritable and have been associated with the risk of clinical thrombotic events. To identify rare and low-frequency variants associated with these hemostatic factors, we conducted whole exome sequencing in 10 860 individuals of European ancestry (EA) and 3529 African Americans (AAs) from the Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) Consortium and the National Heart, Lung, and Blood Institute's Exome Sequencing Project (ESP). Gene-based tests demonstrated significant associations with rare variation (minor allele frequency < 5%) in FGG (with fibrinogen, p = 9.1x10-13), F7 (with factor VII, p = 1.3x10-72; seven novel variants), and VWF (with factor VIII and vWF; p = 3.2x10-14; one novel variant). These eight novel rare variant associations were independent of the known common variants at these loci and tended to have much larger effect sizes. In addition, one of the rare novel variants in F7 was significantly associated with an increased risk of venous thromboembolism in AAs (Ile200Ser; rs141219108; p = 4.2x10-5). After restricting gene-based analyses to only loss-of-function variants, a novel significant association was detected and replicated between factor VIII levels and a stop-gain mutation exclusive to African Americans (rs3211938) in CD36. This variant has previously been linked to dyslipidemia but not with levels of a hemostatic factor. These efforts represent the largest integration of whole exome sequence data from two national projects to identify genetic variation associated with plasma hemostatic factors.

Whole genome sequence association analysis of fasting glucose and fasting insulin levels in diverse cohorts from the NHLBI TOPMed program. - DiCorpo, Daniel; Gaynor, Sheila M; Russell, Emily M; Westerman, Kenneth E; Raffield, Laura M; Majarian, Timothy D; Wu, Peitao; Sarnowski, Chloe; Highland, Heather M; Jackson, Anne; Hasbani, Natalie R; de Vries, Paul S; et al. (Commun Biol, 2022)
The genetic determinants of fasting glucose (FG) and fasting insulin (FI) have been studied mostly through genome arrays, resulting in over 100 associated variants. We extended this work with high-coverage whole genome sequencing analyses from fifteen cohorts in NHLBI's Trans-Omics for Precision Medicine (TOPMed) program. Over 23,000 non-diabetic individuals from five race-ethnicities/populations (African, Asian, European, Hispanic and Samoan) were included. Eight variants were significantly associated with FG or FI across previously identified regions MTNR1B, G6PC2, GCK, GCKR and FOXA2. We additionally characterize suggestive associations with FG or FI near previously identified SLC30A8, TCF7L2, and ADCY5 regions as well as APOB, PTPRT, and ROBO1. Functional annotation resources including the Diabetes Epigenome Atlas were compiled for each signal (chromatin states, annotation principal components, and others) to elucidate variant-to-function hypotheses. We provide a catalog of nucleotide-resolution genomic variation spanning intergenic and intronic regions creating a foundation for future sequencing-based investigations of glycemic traits.
Keywords: Diabetes Mellitus, Type 2; Fasting; Glucose; Humans; Insulin; National Heart, Lung, and Blood Institute (U.S.); Nerve Tissue Proteins; Polymorphism, Single Nucleotide; Precision Medicine; Receptors, Immunologic; United States

Whole genome sequencing identifies structural variants contributing to hematologic traits in the NHLBI TOPMed program. - Wheeler, Marsha M; Stilp, Adrienne M; Rao, Shuquan; Halldorsson, Bjarni V; Beyter, Doruk; Wen, Jia; Mihkaylova, Anna V; McHugh, Caitlin P; Lane, John; Jiang, Min-Zhi; Raffield, Laura M; Jun, Goo; et al. (Nat Commun, 2022)
Genome-wide association studies have identified thousands of single nucleotide variants and small indels that contribute to variation in hematologic traits. While structural variants are known to cause rare blood or hematopoietic disorders, the genome-wide contribution of structural variants to quantitative blood cell trait variation is unknown. Here we utilized whole genome sequencing data in ancestrally diverse participants of the NHLBI Trans Omics for Precision Medicine program (N = 50,675) to detect structural variants associated with hematologic traits. Using single variant tests, we assessed the association of common and rare structural variants with red cell-, white cell-, and platelet-related quantitative traits and observed 21 independent signals (12 common and 9 rare) reaching genome-wide significance. The majority of these associations (N = 18) replicated in independent datasets. In genome-editing experiments, we provide evidence that a deletion associated with lower monocyte counts leads to disruption of an S1PR3 monocyte enhancer and decreased S1PR3 expression.
Keywords: Blood Cells; Genome-Wide Association Study; Humans; Whole Genome Sequencing

{Whole-Genome Sequencing Association Analyses of Stroke and Its Subtypes in Ancestrally Diverse Populations From Trans-Omics for Precision Medicine Project - Hu, Y.; Haessler, J. W.; Manansala, R.; Wiggins, K. L.; Moscati, A.; Beiser, A.; Heard-Costa, N. L.; Sarnowski, C.; Raffield, L. M.; Chung, J.; Marini, S.; Anderson, C. D.; et al. (Stroke, 2022)
Stroke is the leading cause of death and long-term disability worldwide. Previous genome-wide association studies identified 51 loci associated with stroke (mostly ischemic) and its subtypes among predominantly European populations. Using whole-genome sequencing in ancestrally diverse populations from the Trans-Omics for Precision Medicine (TOPMed) Program, we aimed to identify novel variants, especially low-frequency or ancestry-specific variants, associated with all stroke, ischemic stroke and its subtypes (large artery, cardioembolic, and small vessel), and hemorrhagic stroke and its subtypes (intracerebral and subarachnoid).\ Whole-genome sequencing data were available for 6833 stroke cases and 27 116 controls, including 22 315 European, 7877 Black, 2616 Hispanic/Latino, 850 Asian, 54 Native American, and 237 other ancestry participants. In TOPMed, we performed single variant association analysis examining 40 million common variants and aggregated association analysis focusing on rare variants. We also combined TOPMed European populations with over 28 000 additional European participants from the UK BioBank genome-wide array data through meta-analysis.\ .\ We represent the first association analysis for stroke and its subtypes using whole-genome sequencing data from ancestrally diverse populations. While our findings suggest the potential benefits of combining whole-genome sequencing data with populations of diverse genetic backgrounds to identify possible low-frequency or ancestry-specific variants, they also highlight the need to increase genome coverage and sample sizes.

Aberrant activation of TCL1A promotes stem cell expansion in clonal haematopoiesis. - Weinstock, Joshua S; Gopakumar, Jayakrishnan; Burugula, Bala Bharathi; Uddin, Md Mesbah; Jahn, Nikolaus; Belk, Julia A; Bouzid, Hind; Daniel, Bence; Miao, Zhuang; Ly, Nghi; Mack, Taralynn M; Luna, Sofia E; et al. (Nature, 2023)
Mutations in a diverse set of driver genes increase the fitness of haematopoietic stem cells (HSCs), leading to clonal haematopoiesis. These lesions are precursors for blood cancers, but the basis of their fitness advantage remains largely unknown, partly owing to a paucity of large cohorts in which the clonal expansion rate has been assessed by longitudinal sampling. Here, to circumvent this limitation, we developed a method to infer the expansion rate from data from a single time point. We applied this method to 5,071 people with clonal haematopoiesis. A genome-wide association study revealed that a common inherited polymorphism in the TCL1A promoter was associated with a slower expansion rate in clonal haematopoiesis overall, but the effect varied by driver gene. Those carrying this protective allele exhibited markedly reduced growth rates or prevalence of clones with driver mutations in TET2, ASXL1, SF3B1 and SRSF2, but this effect was not seen in clones with driver mutations in DNMT3A. TCL1A was not expressed in normal or DNMT3A-mutated HSCs, but the introduction of mutations in TET2 or ASXL1 led to the expression of TCL1A protein and the expansion of HSCs in vitro. The protective allele restricted TCL1A expression and expansion of mutant HSCs, as did experimental knockdown of TCL1A expression. Forced expression of TCL1A promoted the expansion of human HSCs in vitro and mouse HSCs in vivo. Our results indicate that the fitness advantage of several commonly mutated driver genes in clonal haematopoiesis may be mediated by TCL1A activation.
Keywords: Alleles; Animals; Clonal Hematopoiesis; Genome-Wide Association Study; Hematopoiesis; Hematopoietic Stem Cells; Humans; Mice; Mutation; Promoter Regions, Genetic

Association between 5-year change in cardiovascular risk and the incidence of atherosclerotic cardiovascular diseases: a multi-cohort study. - Yi, Jiayi; Wang, Lili; Guo, Xinli; Ren, Xiangpeng (J Transl Med, 2023)
BACKGROUND: The influence of the historical cardiovascular risk status on future risk of atherosclerotic cardiovascular disease (ASCVD) is poorly understood. We aimed to investigate the association between 5-year changes in cardiovascular risk and ASCVD incidence. METHODS: We analyzed pooled data from seven community-based prospective cohort studies with up to 20 years of follow-up data. The study populations included White or Black participants aged 40-75 years without prevalent ASCVD. Cardiovascular risk was assessed using the pooled cohort equation and was categorized into non-high (< 20%) or high risk (≥ 20%). Changes in cardiovascular disease (CVD) risk over a 5-year interval were recorded. The main outcome was incident ASCVD. RESULTS: Among 11,026 participants (mean [SD] age, 60.0 [8.1] years), 4272 (38.7%) were female and 3127 (28.4%) were Black. During a median follow-up period of 9.9 years, 2560 (23.2%) ASCVD events occurred. In comparison with individuals showing a consistently high CVD risk, participants whose CVD risk changed from non-high to high (hazard ratio [HR], 0.67; 95% confidence interval [CI] 0.59-0.77) or high to non-high (HR, 0.57; 95% CI 0.41-0.80) and those with a consistently non-high risk (HR, 0.33; 95% CI 0.29-0.37) had a lower risk of incident ASCVD. In comparison with individuals showing a consistently non-high CVD risk, participants whose CVD risk changed from high to non-high (HR, 1.74; 95% CI 1.26-2.41) or from non-high to high risk (HR, 2.04; 95% CI 1.84-2.27) and those with a consistently high risk (HR 3.03; 95% CI 2.69-3.42) also showed an increased risk of incident ASCVD. CONCLUSIONS: Individuals with the same current CVD risk status but different historical CVD risks exhibited varying risks of future ASCVD incidents. Dynamic risk evaluation may enable more accurate cardiovascular risk stratification, and decision-making regarding preventive interventions should take the historical risk status into account.
Keywords: Atherosclerosis; Cardiovascular Diseases; Cohort Studies; Female; Heart Disease Risk Factors; Humans; Incidence; Male; Middle Aged; Prospective Studies; Risk Factors

Association Between Acute Myocardial Infarction and Cognition. - Johansen, Michelle C; Ye, Wen; Gross, Alden; Gottesman, Rebecca F; Han, Dehua; Whitney, Rachael; Briceño, Emily M; Giordani, Bruno J; Shore, Supriya; Elkind, Mitchell S V; Manly, Jennifer J; Sacco, Ralph L; et al. (JAMA Neurol, 2023)
IMPORTANCE: The magnitude of cognitive change after incident myocardial infarction (MI) is unclear. OBJECTIVE: To assess whether incident MI is associated with changes in cognitive function after adjusting for pre-MI cognitive trajectories. DESIGN, SETTING, AND PARTICIPANTS: This cohort study included adults without MI, dementia, or stroke and with complete covariates from the following US population-based cohort studies conducted from 1971 to 2019: Atherosclerosis Risk in Communities Study, Coronary Artery Risk Development in Young Adults Study, Cardiovascular Health Study, Framingham Offspring Study, Multi-Ethnic Study of Atherosclerosis, and Northern Manhattan Study. Data were analyzed from July 2021 to January 2022. EXPOSURES: Incident MI. MAIN OUTCOMES AND MEASURES: The main outcome was change in global cognition. Secondary outcomes were changes in memory and executive function. Outcomes were standardized as mean (SD) T scores of 50 (10); a 1-point difference represented a 0.1-SD difference in cognition. Linear mixed-effects models estimated changes in cognition at the time of MI (change in the intercept) and the rate of cognitive change over the years after MI (change in the slope), controlling for pre-MI cognitive trajectories and participant factors, with interaction terms for race and sex. RESULTS: The study included 30 465 adults (mean [SD] age, 64 [10] years; 56% female), of whom 1033 had 1 or more MI event, and 29 432 did not have an MI event. Median follow-up was 6.4 years (IQR, 4.9-19.7 years). Overall, incident MI was not associated with an acute decrease in global cognition (-0.18 points; 95% CI, -0.52 to 0.17 points), executive function (-0.17 points; 95% CI, -0.53 to 0.18 points), or memory (0.62 points; 95% CI, -0.07 to 1.31 points). However, individuals with incident MI vs those without MI demonstrated faster declines in global cognition (-0.15 points per year; 95% CI, -0.21 to -0.10 points per year), memory (-0.13 points per year; 95% CI, -0.22 to -0.04 points per year), and executive function (-0.14 points per year; 95% CI, -0.20 to -0.08 points per year) over the years after MI compared with pre-MI slopes. The interaction analysis suggested that race and sex modified the degree of change in the decline in global cognition after MI (race × post-MI slope interaction term, P = .02; sex × post-MI slope interaction term, P = .04), with a smaller change in the decline over the years after MI in Black individuals than in White individuals (difference in slope change, 0.22 points per year; 95% CI, 0.04-0.40 points per year) and in females than in males (difference in slope change, 0.12 points per year; 95% CI, 0.01-0.23 points per year). CONCLUSIONS: This cohort study using pooled data from 6 cohort studies found that incident MI was not associated with a decrease in global cognition, memory, or executive function at the time of the event compared with no MI but was associated with faster declines in global cognition, memory, and executive function over time. These findings suggest that prevention of MI may be important for long-term brain health.

Association Between Whole Blood-Derived Mitochondrial DNA Copy Number, Low-Density Lipoprotein Cholesterol, and Cardiovascular Disease Risk. - Liu, Xue; Sun, Xianbang; Zhang, Yuankai; Jiang, Wenqing; Lai, Meng; Wiggins, Kerri L; Raffield, Laura M; Bielak, Lawrence F; Zhao, Wei; Pitsillides, Achilleas; Haessler, Jeffrey; Zheng, Yinan; et al. (J Am Heart Assoc, 2023)
Background The relationship between mitochondrial DNA copy number (mtDNA CN) and cardiovascular disease remains elusive. Methods and Results We performed cross-sectional and prospective association analyses of blood-derived mtDNA CN and cardiovascular disease outcomes in 27 316 participants in 8 cohorts of multiple racial and ethnic groups with whole-genome sequencing. We also performed Mendelian randomization to explore causal relationships of mtDNA CN with coronary heart disease (CHD) and cardiometabolic risk factors (obesity, diabetes, hypertension, and hyperlipidemia). <0.01 was used for significance. We validated most of the previously reported associations between mtDNA CN and cardiovascular disease outcomes. For example, 1-SD unit lower level of mtDNA CN was associated with 1.08 (95% CI, 1.04-1.12; <0.001) times the hazard for developing incident CHD, adjusting for covariates. Mendelian randomization analyses showed no causal effect from a lower level of mtDNA CN to a higher CHD risk (β=0.091; =0.11) or in the reverse direction (β=-0.012; =0.076). Additional bidirectional Mendelian randomization analyses revealed that low-density lipoprotein cholesterol had a causal effect on mtDNA CN (β=-0.084; <0.001), but the reverse direction was not significant (=0.059). No causal associations were observed between mtDNA CN and obesity, diabetes, and hypertension, in either direction. Multivariable Mendelian randomization analyses showed no causal effect of CHD on mtDNA CN, controlling for low-density lipoprotein cholesterol level (=0.52), whereas there was a strong direct causal effect of higher low-density lipoprotein cholesterol on lower mtDNA CN, adjusting for CHD status (β=-0.092; <0.001). Conclusions Our findings indicate that high low-density lipoprotein cholesterol may underlie the complex relationships between mtDNA CN and vascular atherosclerosis.

Association of Mitochondrial DNA Copy Number With Brain MRI Markers and Cognitive Function: A Meta-analysis of Community-Based Cohorts. - Zhang, Yuankai; Liu, Xue; Wiggins, Kerri L; Kurniansyah, Nuzulul; Guo, Xiuqing; Rodrigue, Amanda L; Zhao, Wei; Yanek, Lisa R; Ratliff, Scott M; Pitsillides, Achilleas; Aguirre Patiño, Juan Sebastian; Sofer, Tamar; et al. (Neurology, 2023)
BACKGROUND AND OBJECTIVES: Previous studies suggest lower mitochondrial DNA (mtDNA) copy number (CN) is associated with neurodegenerative diseases. However, whether mtDNA CN in whole blood is related to endophenotypes of Alzheimer's disease (AD) and AD related dementia (AD/ADRD) needs further investigation. We assessed the association of mtDNA CN with cognitive function and MRI measures in community-based samples of middle-aged to older adults. METHODS: We included dementia-free participants from nine diverse community-based cohorts with whole-genome sequencing in the Trans-Omics for Precision Medicine (TOPMed) program. Circulating mtDNA CN was estimated as twice the ratio of the average coverage of mtDNA to nuclear DNA. Brain MRI markers included total brain, hippocampal, and white matter hyperintensity volumes. General cognitive function was derived from distinct cognitive domains. We performed cohort-specific association analyses of mtDNA CN with AD/ADRD endophenotypes assessed within ±5 years (i.e., cross-sectional analyses) or 5 to 20 years after blood draw (i.e., prospective analyses) adjusting for potential confounders. We further explored associations stratified by sex and age (<60 vs. ≥60 years). Fixed-effects or sample size-weighted meta-analyses were performed to combine results. Finally, we performed Mendelian randomization (MR) analyses to assess causality. RESULTS: We included up to 19,152 participants (mean age 59 years, 57% women). Higher mtDNA CN was cross-sectionally associated with better general cognitive function (Beta=0.04; 95% CI 0.02, 0.06) independent of age, sex, batch effects, race/ethnicity, time between blood draw and cognitive evaluation, cohort-specific variables, and education. Additional adjustment for blood cell counts or cardiometabolic traits led to slightly attenuated results. We observed similar significant associations with cognition in prospective analyses, although of reduced magnitude. We found no significant associations between mtDNA CN and brain MRI measures in meta-analyses. MR analyses did not reveal a causal relation between mtDNA CN in blood and cognition. DISCUSSION: Higher mtDNA CN in blood is associated with better current and future general cognitive function in large and diverse communities across the US. Although MR analyses did not support a causal role, additional research is needed to assess causality. Circulating mtDNA CN could serve nevertheless as a biomarker of current and future cognitive function in the community.

Association of Obesity With Cognitive Decline in Black and White Americans. - Quaye, Emmanuel; Galecki, Andrzej T; Tilton, Nicholas; Whitney, Rachael; Briceño, Emily M; Elkind, Mitchell S V; Fitzpatrick, Annette L; Gottesman, Rebecca F; Griswold, Michael; Gross, Alden L; Heckbert, Susan R; Hughes, Timothy M; et al. (Neurology, 2023)
BACKGROUND AND OBJECTIVES: There are disparities in the prevalence of obesity by race, and the relationship between obesity and cognitive decline is unclear. The objective of this study was to determine whether obesity is independently associated with cognitive decline and whether the association between obesity and cognitive decline differs in Black and White adults. We hypothesized that obesity is associated with greater cognitive decline compared with normal weight and that the effect of obesity on cognitive decline is more pronounced in Black adults compared with their White counterparts. METHODS: We pooled data from 28,867 participants free of stroke and dementia (mean, SD: age 61 [10.7] years at the first cognitive assessment, 55% female, 24% Black, and 29% obese) from 6 cohorts. The primary outcome was the annual change in global cognition. We performed linear mixed-effects models with and without time-varying cumulative mean systolic blood pressure (SBP) and fasting plasma glucose (FPG). Global cognition was set to a t-score metric (mean 50, SD 10) at a participant's first cognitive assessment; a 1-point difference represents a 0.1 SD difference in global cognition across the 6 cohorts. The median follow-up was 6.5 years (25th percentile, 75th percentile: 5.03, 20.15). RESULTS: Obese participants had lower baseline global cognition than normal-weight participants (difference in intercepts, -0.36 [95% CI, -0.46 to -0.17]; < 0.001). This difference in baseline global cognition was attenuated but was borderline significant after accounting for SBP and FPG (adjusted differences in intercepts, -0.19 [95% CI, -0.39 to 0.002]; = 0.05). There was no difference in the rate of decline in global cognition between obese and normal-weight participants (difference in slope, 0.009 points/year [95% CI, -0.009 to 0.03]; = 0.32). After accounting for SBP and FPG, obese participants had a slower decline in global cognition (adjusted difference in slope, 0.03 points/year slower [95% CI, 0.01 to 0.05]; < 0.001). There was no evidence that race modified the association between body mass index and global cognitive decline ( = 0.34). DISCUSSION: These results suggest that obesity is associated with lower initial cognitive scores and may potentially attenuate declines in cognition after accounting for BP and FPG.
Keywords: Aged; Black or African American; Cognition; Cognitive Dysfunction; Female; Humans; Male; Middle Aged; Obesity; Risk Factors; United States; White

Association of omega 3 polyunsaturated fatty acids with incident chronic kidney disease: pooled analysis of 19 cohorts. - Ong, Kwok Leung; Marklund, Matti; Huang, Liping; Rye, Kerry-Anne; Hui, Nicholas; Pan, Xiong-Fei; Rebholz, Casey M; Kim, Hyunju; Steffen, Lyn M; van Westing, Anniek C; Geleijnse, Johanna M; Hoogeveen, Ellen K; et al. (BMJ, 2023)
OBJECTIVE: To assess the prospective associations of circulating levels of omega 3 polyunsaturated fatty acid (n-3 PUFA) biomarkers (including plant derived α linolenic acid and seafood derived eicosapentaenoic acid, docosapentaenoic acid, and docosahexaenoic acid) with incident chronic kidney disease (CKD). DESIGN: Pooled analysis. DATA SOURCES: A consortium of 19 studies from 12 countries identified up to May 2020. STUDY SELECTION: Prospective studies with measured n-3 PUFA biomarker data and incident CKD based on estimated glomerular filtration rate. DATA EXTRACTION AND SYNTHESIS: Each participating cohort conducted de novo analysis with prespecified and consistent exposures, outcomes, covariates, and models. The results were pooled across cohorts using inverse variance weighted meta-analysis. MAIN OUTCOME MEASURES: Primary outcome of incident CKD was defined as new onset estimated glomerular filtration rate <60 mL/min/1.73 m. In a sensitivity analysis, incident CKD was defined as new onset estimated glomerular filtration rate <60 mL/min/1.73 m and <75% of baseline rate. RESULTS: 25 570 participants were included in the primary outcome analysis and 4944 (19.3%) developed incident CKD during follow-up (weighted median 11.3 years). In multivariable adjusted models, higher levels of total seafood n-3 PUFAs were associated with a lower incident CKD risk (relative risk per interquintile range 0.92, 95% confidence interval 0.86 to 0.98; P=0.009, I=9.9%). In categorical analyses, participants with total seafood n-3 PUFA level in the highest fifth had 13% lower risk of incident CKD compared with those in the lowest fifth (0.87, 0.80 to 0.96; P=0.005, I=0.0%). Plant derived α linolenic acid levels were not associated with incident CKD (1.00, 0.94 to 1.06; P=0.94, I=5.8%). Similar results were obtained in the sensitivity analysis. The association appeared consistent across subgroups by age (≥60 <60 years), estimated glomerular filtration rate (60-89 ≥90 mL/min/1.73 m), hypertension, diabetes, and coronary heart disease at baseline. CONCLUSIONS: Higher seafood derived n-3 PUFA levels were associated with lower risk of incident CKD, although this association was not found for plant derived n-3 PUFAs. These results support a favourable role for seafood derived n-3 PUFAs in preventing CKD.
Keywords: alpha-Linolenic Acid; Fatty Acids, Omega-3; Fatty Acids, Unsaturated; Humans; Middle Aged; Prospective Studies; Renal Insufficiency, Chronic; Risk Factors

Association of Rare Protein-Truncating DNA Variants in APOB or PCSK9 With Low-density Lipoprotein Cholesterol Level and Risk of Coronary Heart Disease. - Dron, Jacqueline S; Patel, Aniruddh P; Zhang, Yiyi; Jurgens, Sean J; Maamari, Dimitri J; Wang, Minxian; Boerwinkle, Eric; Morrison, Alanna C; de Vries, Paul S; Fornage, Myriam; Hou, Lifang; Lloyd-Jones, Donald M; et al. (JAMA Cardiol, 2023)
IMPORTANCE: Protein-truncating variants (PTVs) in apolipoprotein B (APOB) and proprotein convertase subtilisin/kexin type 9 (PCSK9) are associated with significantly lower low-density lipoprotein (LDL) cholesterol concentrations. The association of these PTVs with coronary heart disease (CHD) warrants further characterization in large, multiracial prospective cohort studies. OBJECTIVE: To evaluate the association of PTVs in APOB and PCSK9 with LDL cholesterol concentrations and CHD risk. DESIGN, SETTING, AND PARTICIPANTS: This studied included participants from 5 National Heart, Lung, and Blood Institute (NHLBI) studies and the UK Biobank. NHLBI study participants aged 5 to 84 years were recruited between 1971 and 2002 across the US and underwent whole-genome sequencing. UK Biobank participants aged 40 to 69 years were recruited between 2006 and 2010 in the UK and underwent whole-exome sequencing. Data were analyzed from June 2021 to October 2022. EXPOSURES: PTVs in APOB and PCSK9. MAIN OUTCOMES AND MEASURES: Estimated untreated LDL cholesterol levels and CHD. RESULTS: Among 19 073 NHLBI participants (10 598 [55.6%] female; mean [SD] age, 52 [17] years), 139 (0.7%) carried an APOB or PCSK9 PTV, which was associated with 49 mg/dL (95% CI, 43-56) lower estimated untreated LDL cholesterol level. Over a median (IQR) follow-up of 21.5 (13.9-29.4) years, incident CHD was observed in 12 of 139 carriers (8.6%) vs 3029 of 18 934 noncarriers (16.0%), corresponding to an adjusted hazard ratio of 0.51 (95% CI, 0.28-0.89; P = .02). Among 190 464 UK Biobank participants (104 831 [55.0%] female; mean [SD] age, 57 [8] years), 662 (0.4%) carried a PTV, which was associated with 45 mg/dL (95% CI, 42-47) lower estimated untreated LDL cholesterol level. Estimated CHD risk by age 75 years was 3.7% (95% CI, 2.0-5.3) in carriers vs 7.0% (95% CI, 6.9-7.2) in noncarriers, corresponding to an adjusted hazard ratio of 0.51 (95% CI, 0.32-0.81; P = .004). CONCLUSIONS AND RELEVANCE: Among 209 537 individuals in this study, 0.4% carried an APOB or PCSK9 PTV that was associated with less exposure to LDL cholesterol and a 49% lower risk of CHD.

Association of Severe Hypercholesterolemia and Familial Hypercholesterolemia Genotype With Risk of Coronary Heart Disease. - Zhang, Yiyi; Dron, Jacqueline S; Bellows, Brandon K; Khera, Amit V; Liu, Junxiu; Balte, Pallavi P; Oelsner, Elizabeth C; Amr, Sami Samir; Lebo, Matthew S; Nagy, Anna; Peloso, Gina M; Natarajan, Pradeep; et al. (Circulation, 2023)
Keywords: Coronary Disease; Genotype; Humans; Hypercholesterolemia; Hyperlipoproteinemia Type II

{Associations Between Vascular Risk Factor Levels and Cognitive Decline Among Stroke Survivors - Levine, D. A.; Chen, B.; Galecki, A. T.; Gross, A. L.; o, E. M.; Whitney, R. T.; Ploutz-Snyder, R. J.; Giordani, B. J.; Sussman, J. B.; Burke, J. F.; Lazar, R. M.; Howard, V. J.; et al. (JAMA Netw Open, 2023)
Incident stroke is associated with accelerated cognitive decline. Whether poststroke vascular risk factor levels are associated with faster cognitive decline is uncertain.\ To evaluate associations of poststroke systolic blood pressure (SBP), glucose, and low-density lipoprotein (LDL) cholesterol levels with cognitive decline.\ Individual participant data meta-analysis of 4 US cohort studies (conducted 1971-2019). Linear mixed-effects models estimated changes in cognition after incident stroke. Median (IQR) follow-up was 4.7 (2.6-7.9) years. Analysis began August 2021 and was completed March 2023.\ Time-dependent cumulative mean poststroke SBP, glucose, and LDL cholesterol levels.\ The primary outcome was change in global cognition. Secondary outcomes were change in executive function and memory. Outcomes were standardized as t scores (mean [SD], 50 [10]); a 1-point difference represents a 0.1-SD difference in cognition.\ .002) but not executive function or memory declines.\ In this cohort study, higher poststroke glucose levels were associated with faster global cognitive decline. We found no evidence that poststroke LDL cholesterol and SBP levels were associated with cognitive decline.

Carriers of rare damaging genetic variants are at lower risk of atherosclerotic disease. - Georgakis, Marios K; Malik, Rainer; Hasbani, Natalie R; Shakt, Gabrielle; Morrison, Alanna C; Tsao, Noah L; Judy, Renae; Mitchell, Braxton D; Xu, Huichun; Montasser, May E; Do, Ron; Kenny, Eimear E; et al. (medRxiv, 2023)
BACKGROUND: The CCL2/CCR2 axis governs monocyte trafficking and recruitment to atherosclerotic lesions. Human genetic analyses and population-based studies support an association between circulating CCL2 levels and atherosclerosis. Still, it remains unknown whether pharmacological targeting of CCR2, the main CCL2 receptor, would provide protection against human atherosclerotic disease. METHODS: In whole-exome sequencing data from 454,775 UK Biobank participants (40-69 years), we identified predicted loss-of-function (LoF) or damaging missense (REVEL score >0.5) variants within the gene. We prioritized variants associated with lower monocyte count (p<0.05) and tested associations with vascular risk factors and risk of atherosclerotic disease over a mean follow-up of 14 years. The results were replicated in a pooled cohort of three independent datasets (TOPMed, deCODE and Penn Medicine BioBank; total n=441,445) and the effect of the most frequent damaging variant was experimentally validated. RESULTS: A total of 45 predicted LoF or damaging missense variants were identified in the gene, 4 of which were also significantly associated with lower monocyte count, but not with other white blood cell counts. Heterozygous carriers of these variants were at a lower risk of a combined atherosclerosis outcome, showed a lower burden of atherosclerosis across four vascular beds, and were at a lower lifetime risk of coronary artery disease and myocardial infarction. There was no evidence of association with vascular risk factors including LDL-cholesterol, blood pressure, glycemic status, or C-reactive protein. Using a cAMP assay, we found that cells transfected with the most frequent damaging variant (3:46358273:T:A, M249K, 547 carriers, frequency: 0.14%) show a decrease in signaling in response to CCL2. The associations of the M249K variant with myocardial infarction were consistent across cohorts (OR : 0.62 95%CI: 0.39-0.96; OR : 0.64 95%CI: 0.34-1.19; OR : 0.64 95%CI: 0.45-0.90). In a phenome-wide association study, we found no evidence for higher risk of common infections or mortality among carriers of damaging variants. CONCLUSIONS: Heterozygous carriers of damaging variants have a lower burden of atherosclerosis and lower lifetime risk of myocardial infarction. In conjunction with previous evidence from experimental and epidemiological studies, our findings highlight the translational potential of CCR2-targeting as an atheroprotective approach.

Clonal hematopoiesis is associated with protection from Alzheimer's disease. - Bouzid, Hind; Belk, Julia A; Jan, Max; Qi, Yanyan; Sarnowski, Chloe; Wirth, Sara; Ma, Lisa; Chrostek, Matthew R; Ahmad, Herra; Nachun, Daniel; Yao, Winnie; Beiser, Alexa; et al. (Nat Med, 2023)
Clonal hematopoiesis of indeterminate potential (CHIP) is a premalignant expansion of mutated hematopoietic stem cells. As CHIP-associated mutations are known to alter the development and function of myeloid cells, we hypothesized that CHIP may also be associated with the risk of Alzheimer's disease (AD), a disease in which brain-resident myeloid cells are thought to have a major role. To perform association tests between CHIP and AD dementia, we analyzed blood DNA sequencing data from 1,362 individuals with AD and 4,368 individuals without AD. Individuals with CHIP had a lower risk of AD dementia (meta-analysis odds ratio (OR) = 0.64, P = 3.8 × 10), and Mendelian randomization analyses supported a potential causal association. We observed that the same mutations found in blood were also detected in microglia-enriched fraction of the brain in seven of eight CHIP carriers. Single-nucleus chromatin accessibility profiling of brain-derived nuclei in six CHIP carriers revealed that the mutated cells comprised a large proportion of the microglial pool in the samples examined. While additional studies are required to validate the mechanistic findings, these results suggest that CHIP may have a role in attenuating the risk of AD.

Clonal Hematopoiesis of Indeterminate Potential (CHIP) and Incident Type 2 Diabetes Risk. - Tobias, Deirdre K; Manning, Alisa K; Wessel, Jennifer; Raghavan, Sridharan; Westerman, Kenneth E; Bick, Alexander G; DiCorpo, Daniel; Whitsel, Eric A; Collins, Jason; Correa, Adolfo; Cupples, L Adrienne; Dupuis, Josée; et al. (Diabetes Care, 2023)
OBJECTIVE: Clonal hematopoiesis of indeterminate potential (CHIP) is an aging-related accumulation of somatic mutations in hematopoietic stem cells, leading to clonal expansion. CHIP presence has been implicated in atherosclerotic coronary heart disease (CHD) and all-cause mortality, but its association with incident type 2 diabetes (T2D) is unknown. We hypothesized that CHIP is associated with elevated risk of T2D. RESEARCH DESIGN AND METHODS: CHIP was derived from whole-genome sequencing of blood DNA in the National Heart, Lung, and Blood Institute Trans-Omics for Precision Medicine (TOPMed) prospective cohorts. We performed analysis for 17,637 participants from six cohorts, without prior T2D, cardiovascular disease, or cancer. We evaluated baseline CHIP versus no CHIP prevalence with incident T2D, including associations with DNMT3A, TET2, ASXL1, JAK2, and TP53 variants. We estimated multivariable-adjusted hazard ratios (HRs) and 95% confidence intervals (CIs) with adjustment for age, sex, BMI, smoking, alcohol, education, self-reported race/ethnicity, and combined cohorts' estimates via fixed-effects meta-analysis. RESULTS: Mean (SD) age was 63.4 (11.5) years, 76% were female, and CHIP prevalence was 6.0% (n = 1,055) at baseline. T2D was diagnosed in n = 2,467 over mean follow-up of 9.8 years. Participants with CHIP had 23% (CI = 1.04, 1.45) higher risk of T2D than those with no CHIP. Specifically, higher risk was for TET2 (HR 1.48; CI = 1.05, 2.08) and ASXL1 (HR 1.76; CI = 1.03, 2.99) mutations; DNMT3A was nonsignificant (HR 1.15; CI = 0.93, 1.43). Statistical power was limited for JAK2 and TP53 analyses. CONCLUSIONS: CHIP was associated with higher incidence of T2D. CHIP mutations located on genes implicated in CHD and mortality were also related to T2D, suggesting shared aging-related pathology.

Clonal Hematopoiesis of Indeterminate Potential is Associated with Acute Kidney Injury. - Vlasschaert, Caitlyn; Robinson-Cohen, Cassianne; Kestenbaum, Bryan; Silver, Samuel A; Chen, Jian-Chun; Akwo, Elvis; Bhatraju, Pavan K; Zhang, Ming-Zhi; Cao, Shirong; Jiang, Ming; Wang, Yinqiu; Niu, Aolei; et al. (medRxiv, 2023)
Age is a predominant risk factor for acute kidney injury (AKI), yet the biological mechanisms underlying this risk are largely unknown and to date no genetic mechanisms for AKI have been established. Clonal hematopoiesis of indeterminate potential (CHIP) is a recently recognized biological mechanism conferring risk of several chronic aging diseases including cardiovascular disease, pulmonary disease and liver disease. In CHIP, blood stem cells acquire mutations in myeloid cancer driver genes such as and and the myeloid progeny of these mutated cells contribute to end-organ damage through inflammatory dysregulation. We sought to establish whether CHIP causes acute kidney injury (AKI). To address this question, we first evaluated associations with incident AKI events in three population-based epidemiology cohorts (N = 442,153). We found that CHIP was associated with a greater risk of AKI (adjusted HR 1.26, 95% CI: 1.19-1.34, p<0.0001), which was more pronounced in patients with AKI requiring dialysis (adjusted HR 1.65, 95% CI: 1.24-2.20, p=0.001). The risk was particularly high in the subset of individuals where CHIP was driven by mutations in genes other than (HR: 1.49, 95% CI: 1.37-1.61, p<0.0001). We then examined the association between CHIP and recovery from AKI in the ASSESS-AKI cohort and identified that non- CHIP was more common among those with a non-resolving pattern of injury (HR 2.3, 95% CI: 1.14-4.64, p = 0.03). To gain mechanistic insight, we evaluated the role of -CHIP to AKI in ischemia-reperfusion injury (IRI) and unilateral ureteral obstruction (UUO) mouse models. In both models, we observed more severe AKI and greater post-AKI kidney fibrosis in -CHIP mice. Kidney macrophage infiltration was markedly increased in -CHIP mice and -CHIP mutant renal macrophages displayed greater pro-inflammatory responses. In summary, this work establishes CHIP as a genetic mechanism conferring risk of AKI and impaired kidney function recovery following AKI via an aberrant inflammatory response in CHIP derived renal macrophages.

Complexities of cerebral small vessel disease, blood pressure, and dementia relationship: new insights from genetics. - Sargurupremraj, Muralidharan; Soumaré, Aïcha; Bis, Joshua C; Surakka, Ida; Jürgenson, Tuuli; Joly, Pierre; Knol, Maria J; Wang, Ruiqi; Yang, Qiong; Satizabal, Claudia L; Gudjonsson, Alexander; Mishra, Aniket; et al. (medRxiv, 2023)
IMPORTANCE: There is increasing recognition that vascular disease, which can be treated, is a key contributor to dementia risk. However, the contribution of specific markers of vascular disease is unclear and, as a consequence, optimal prevention strategies remain unclear. OBJECTIVE: To disentangle the causal relation of several key vascular traits to dementia risk: (i) white matter hyperintensity (WMH) burden, a highly prevalent imaging marker of covert cerebral small vessel disease (cSVD); (ii) clinical stroke; and (iii) blood pressure (BP), the leading risk factor for cSVD and stroke, for which efficient therapies exist. To account for potential epidemiological biases inherent to late-onset conditions like dementia. DESIGN SETTING AND PARTICIPANTS: This study first explored the association of genetically determined WMH, BP levels and stroke risk with AD using summary-level data from large genome-wide association studies (GWASs) in a two-sample Mendelian randomization (MR) framework. Second, leveraging individual-level data from large longitudinal population-based cohorts and biobanks with prospective dementia surveillance, the association of weighted genetic risk scores (wGRSs) for WMH, BP, and stroke with incident all-cause-dementia was explored using Cox-proportional hazard and multi-state models. The data analysis was performed from July 26, 2020, through July 24, 2022. EXPOSURES: Genetically determined levels of WMH volume and BP (systolic, diastolic and pulse blood pressures) and genetic liability to stroke. MAIN OUTCOMES AND MEASURES: The summary-level MR analyses focused on the outcomes from GWAS of clinically diagnosed AD (n-cases=21,982) and GWAS additionally including self-reported parental history of dementia as a proxy for AD diagnosis (AD , n-cases=53,042). For the longitudinal analyses, individual-level data of 157,698 participants with 10,699 incident all-cause-dementia were studied, exploring AD, vascular or mixed dementia in secondary analyses. RESULTS: In the two-sample MR analyses, WMH showed strong evidence for a causal association with increased risk of AD (OR, 1.16; 95%CI:1.05-1.28; P=.003) and AD (OR, 1.28; 95%CI:1.07-1.53; P=.008), after accounting for genetically determined pulse pressure for the latter. Genetically predicted BP traits showed evidence for a protective association with both clinically defined AD and AD , with evidence for confounding by shared genetic instruments. In longitudinal analyses the wGRSs for WMH, but not BP or stroke, showed suggestive association with incident all-cause-dementia (HR, 1.02; 95%CI:1.00-1.04; P=.06). BP and stroke wGRSs were strongly associated with mortality but there was no evidence for selective survival bias during follow-up. In secondary analyses, polygenic scores with more liberal instrument definition showed association of both WMH and stroke with all-cause-dementia, AD, and vascular or mixed dementia; associations of stroke, but not WMH, with dementia outcomes were markedly attenuated after adjusting for interim stroke. CONCLUSION: These findings provide converging evidence that WMH is a leading vascular contributor to dementia risk, which may better capture the brain damage caused by BP (and other etiologies) than BP itself and should be targeted in priority for dementia prevention in the population. KEY POINTS: Do instrumental variable analyses leveraging genetic information provide evidence for a causal association of various vascular traits with Alzheimer's disease (AD) and all-cause-dementia? How do these associations compare for white matter hyperintensity (WMH) burden, a highly prevalent marker of covert cerebral small vessel disease (cSVD), stroke, and blood pressure traits, the strongest known risk factor for cSVD and stroke? Using Mendelian randomization (MR) leveraging large, published genome-wide association studies, this study showed a putative causal association of larger WMH burden with increased AD risk after accounting for pulse pressure effects, and some evidence for association of lower BP with AD risk with possible confounding by shared genetic instruments. Longitudinal analyses on individual-level data also supported association of genetically determined WMH with incident all-cause-dementia and AD, independently of interim stroke. This study using complementary genetic epidemiology approaches, identified increasing WMH burden to be associated with dementia and AD risk, suggesting the association as specific for cSVD and independent of BP and stroke.

Determinants of mosaic chromosomal alteration fitness. - Pershad, Yash; Mack, Taralynn; Poisner, Hannah; Jakubek, Yasminka A; Stilp, Adrienne M; Mitchell, Braxton D; Lewis, Joshua P; Boerwinkle, Eric; Loos, Ruth J; Chami, Nathalie; Wang, Zhe; Barnes, Kathleen; et al. (medRxiv, 2023)
Clonal hematopoiesis (CH) is characterized by the acquisition of a somatic mutation in a hematopoietic stem cell that results in a clonal expansion. These driver mutations can be single nucleotide variants in cancer driver genes or larger structural rearrangements called mosaic chromosomal alterations (mCAs). The factors that influence the variations in mCA fitness and ultimately result in different clonal expansion rates are not well-understood. We used the Passenger-Approximated Clonal Expansion Rate (PACER) method to estimate clonal expansion rate for 6,381 individuals in the NHLBI TOPMed cohort with gain, loss, and copy-neutral loss of heterozygosity mCAs. Our estimates of mCA fitness were correlated (R = 0.49) with an alternative approach that estimated fitness of mCAs in the UK Biobank using a theoretical probability distribution. Individuals with lymphoid-associated mCAs had a significantly higher white blood cell count and faster clonal expansion rate. In a cross-sectional analysis, genome-wide association study of estimates of mCA expansion rate identified , , and locus variants as modulators of mCA clonal expansion rate.

Effect of 2022 ACC/AHA/HFSA Criteria on Stages of Heart Failure in a Pooled Community Cohort. - Mohebi, Reza; Wang, Dongyu; Lau, Emily S; Parekh, Juhi K; Allen, Norrina; Psaty, Bruce M; Benjamin, Emelia J; Levy, Daniel; Wang, Thomas J; Shah, Sanjiv J; Gottdiener, John S; Januzzi, James L; et al. (J Am Coll Cardiol, 2023)
BACKGROUND: The 2022 American College of Cardiology (ACC)/American Heart Association (AHA)/Heart Failure Society of America (HFSA) clinical practice guideline proposed an updated definition for heart failure (HF) stages. OBJECTIVES: This study aimed to compare prevalence and prognosis of HF stages according to classification/definition originally described in 2013 and 2022 ACC/AHA/HFSA definitions. METHODS: Study participants from 3 longitudinal cohorts (the MESA [Multi-Ethnic Study of Atherosclerosis], CHS [Cardiovascular Health Study], and the FHS [Framingham Heart Study]), were categorized into 4 HF stages according to the 2013 and 2022 criteria. Cox proportional hazards regression was used to assess predictors of progression to symptomatic HF and adverse clinical outcomes associated with each HF stage. RESULTS: Among 11,618 study participants, according to the 2022 staging, 1,943 (16.7%) were healthy, 4,348 (37.4%) were in stage A (at risk), 5,019 (43.2%) were in stage B (pre-HF), and 308 (2.7%) were in stage C/D (symptomatic HF). Compared to the classification/definition originally described in 2013, the 2022 ACC/AHA/HFSA approach resulted in a higher proportion of individuals with stage B HF (increase from 15.9% to 43.2%); this shift disproportionately involved women as well as Hispanic and Black individuals. Despite the 2022 criteria designating a greater proportion of individuals as stage B, the relative risk of progression to symptomatic HF remained similar (HR: 10.61; 95% CI: 9.00-12.51; P < 0.001). CONCLUSIONS: New standards for HF staging resulted in a substantial shift of community-based individuals from stage A to stage B. Those with stage B HF in the new system were at high risk for progression to symptomatic HF.
Keywords: American Heart Association; Atherosclerosis; Cardiology; Female; Heart Failure; Humans; Longitudinal Studies; Prognosis; United States

Evaluating the use of blood pressure polygenic risk scores across race/ethnic background groups. - Kurniansyah, Nuzulul; Goodman, Matthew O; Khan, Alyna T; Wang, Jiongming; Feofanova, Elena; Bis, Joshua C; Wiggins, Kerri L; Huffman, Jennifer E; Kelly, Tanika; Elfassy, Tali; Guo, Xiuqing; Palmas, Walter; et al. (Nat Commun, 2023)
We assess performance and limitations of polygenic risk scores (PRSs) for multiple blood pressure (BP) phenotypes in diverse population groups. We compare "clumping-and-thresholding" (PRSice2) and LD-based (LDPred2) methods to construct PRSs from each of multiple GWAS, as well as multi-PRS approaches that sum PRSs with and without weights, including PRS-CSx. We use datasets from the MGB Biobank, TOPMed study, UK biobank, and from All of Us to train, assess, and validate PRSs in groups defined by self-reported race/ethnic background (Asian, Black, Hispanic/Latino, and White). For both SBP and DBP, the PRS-CSx based PRS, constructed as a weighted sum of PRSs developed from multiple independent GWAS, perform best across all race/ethnic backgrounds. Stratified analysis in All of Us shows that PRSs are better predictive of BP in females compared to males, individuals without obesity, and middle-aged (40-60 years) compared to older and younger individuals.
Keywords: Blood Pressure; Ethnicity; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Male; Multifactorial Inheritance; Population Health; Risk Factors

Factors Associated With Circulating Sex Hormones in Men : Individual Participant Data Meta-analyses. - Marriott, Ross J; Murray, Kevin; Adams, Robert J; Antonio, Leen; Ballantyne, Christie M; Bauer, Douglas C; Bhasin, Shalender; Biggs, Mary L; Cawthon, Peggy M; Couper, David J; Dobs, Adrian S; Flicker, Leon; et al. (Ann Intern Med, 2023)
BACKGROUND: Various factors modulate circulating testosterone in men, affecting interpretation of testosterone measurements. PURPOSE: To clarify factors associated with variations in sex hormone concentrations. DATA SOURCES: Systematic literature searches (to July 2019). STUDY SELECTION: Prospective cohort studies of community-dwelling men with total testosterone measured using mass spectrometry. DATA EXTRACTION: Individual participant data (IPD) (9 studies;  = 21 074) and aggregate data (2 studies;  = 4075). Sociodemographic, lifestyle, and health factors and concentrations of total testosterone, sex hormone-binding globulin (SHBG), luteinizing hormone (LH), dihydrotestosterone, and estradiol were extracted. DATA SYNTHESIS: Two-stage random-effects IPD meta-analyses found a nonlinear association of testosterone with age, with negligible change among men aged 17 to 70 years (change per SD increase about the midpoint, -0.27 nmol/L [-7.8 ng/dL] [CI, -0.71 to 0.18 nmol/L {-20.5 to 5.2 ng/dL}]) and decreasing testosterone levels with age for men older than 70 years (-1.55 nmol/L [-44.7 ng/dL] [CI, -2.05 to -1.06 nmol/L {-59.1 to -30.6 ng/dL}]). Testosterone was inversely associated with body mass index (BMI) (change per SD increase, -2.42 nmol/L [-69.7 ng/dL] [CI, -2.70 to -2.13 nmol/L {-77.8 to -61.4 ng/dL}]). Testosterone concentrations were lower for men who were married (mean difference, -0.57 nmol/L [-16.4 ng/dL] [CI, -0.89 to -0.26 nmol/L {-25.6 to -7.5 ng/dL}]); undertook at most 75 minutes of vigorous physical activity per week (-0.51 nmol/L [-14.7 ng/dL] [CI, -0.90 to -0.13 nmol/L {-25.9 to -3.7 ng/dL}]); were former smokers (-0.34 nmol/L [-9.8 ng/dL] [CI, -0.55 to -0.12 nmol/L {-15.9 to -3.5 ng/dL}]); or had hypertension (-0.53 nmol/L [-15.3 ng/dL] [CI, -0.82 to -0.24 nmol/L {-23.6 to -6.9 ng/dL}]), cardiovascular disease (-0.35 nmol/L [-10.1 ng/dL] [CI, -0.55 to -0.15 nmol/L {-15.9 to -4.3 ng/dL}]), cancer (-1.39 nmol/L [-40.1 ng/dL] [CI, -1.79 to -0.99 nmol/L {-51.6 to -28.5 ng/dL}]), or diabetes (-1.43 nmol/L [-41.2 ng/dL] [CI, -1.65 to -1.22 nmol/L {-47.6 to -35.2 ng/dL}]). Sex hormone-binding globulin was directly associated with age and inversely associated with BMI. Luteinizing hormone was directly associated with age in men older than 70 years. LIMITATION: Cross-sectional analysis, heterogeneity between studies and in timing of blood sampling, and imputation for missing data. CONCLUSION: Multiple factors are associated with variation in male testosterone, SHBG, and LH concentrations. Reduced testosterone and increased LH concentrations may indicate impaired testicular function after age 70 years. Interpretation of individual testosterone measurements should account particularly for age older than 70 years, obesity, diabetes, and cancer. PRIMARY FUNDING SOURCE: Medical Research Future Fund, Government of Western Australia, and Lawley Pharmaceuticals. (PROSPERO: CRD42019139668).

Gene-educational attainment interactions in a multi-population genome-wide meta-analysis identify novel lipid loci. - de Las Fuentes, Lisa; Schwander, Karen L; Brown, Michael R; Bentley, Amy R; Winkler, Thomas W; Sung, Yun Ju; Munroe, Patricia B; Miller, Clint L; Aschard, Hugo; Aslibekyan, Stella; Bartz, Traci M; Bielak, Lawrence F; et al. (Front Genet, 2023)
Educational attainment, widely used in epidemiologic studies as a surrogate for socioeconomic status, is a predictor of cardiovascular health outcomes. A two-stage genome-wide meta-analysis of low-density lipoprotein cholesterol (LDL), high-density lipoprotein cholesterol (HDL), and triglyceride (TG) levels was performed while accounting for gene-educational attainment interactions in up to 226,315 individuals from five population groups. We considered two educational attainment variables: "Some College" (yes/no, for any education beyond high school) and "Graduated College" (yes/no, for completing a 4-year college degree). Genome-wide significant ( < 5 × 10) and suggestive ( < 1 × 10) variants were identified in Stage 1 (in up to 108,784 individuals) through genome-wide analysis, and those variants were followed up in Stage 2 studies (in up to 117,531 individuals). In combined analysis of Stages 1 and 2, we identified 18 novel lipid loci (nine for LDL, seven for HDL, and two for TG) by two degree-of-freedom (2 DF) joint tests of main and interaction effects. Four loci showed significant interaction with educational attainment. Two loci were significant only in cross-population analyses. Several loci include genes with known or suggested roles in adipose (), brain (), and liver () biology, highlighting the potential importance of brain-adipose-liver communication in the regulation of lipid metabolism. An investigation of the potential druggability of genes in identified loci resulted in five gene targets shown to interact with drugs approved by the Food and Drug Administration, including genes with roles in adipose and brain tissue. Genome-wide interaction analysis of educational attainment identified novel lipid loci not previously detected by analyses limited to main genetic effects.

Genetic architecture of spatial electrical biomarkers for cardiac arrhythmia and relationship with cardiovascular disease. - Young, William J; Haessler, Jeffrey; Benjamins, Jan-Walter; Repetto, Linda; Yao, Jie; Isaacs, Aaron; Harper, Andrew R; Ramirez, Julia; Garnier, Sophie; Van Duijvenboden, Stefan; Baldassari, Antoine R; Concas, Maria Pina; et al. (Nat Commun, 2023)
The 3-dimensional spatial and 2-dimensional frontal QRS-T angles are measures derived from the vectorcardiogram. They are independent risk predictors for arrhythmia, but the underlying biology is unknown. Using multi-ancestry genome-wide association studies we identify 61 (58 previously unreported) loci for the spatial QRS-T angle (N = 118,780) and 11 for the frontal QRS-T angle (N = 159,715). Seven out of the 61 spatial QRS-T angle loci have not been reported for other electrocardiographic measures. Enrichments are observed in pathways related to cardiac and vascular development, muscle contraction, and hypertrophy. Pairwise genome-wide association studies with classical ECG traits identify shared genetic influences with PR interval and QRS duration. Phenome-wide scanning indicate associations with atrial fibrillation, atrioventricular block and arterial embolism and genetically determined QRS-T angle measures are associated with fascicular and bundle branch block (and also atrioventricular block for the frontal QRS-T angle). We identify potential biology involved in the QRS-T angle and their genetic relationships with cardiovascular traits and diseases, may inform future research and risk prediction.
Keywords: Arrhythmias, Cardiac; Atrioventricular Block; Biomarkers; Cardiovascular Diseases; Electrocardiography; Genome-Wide Association Study; Humans; Risk Factors

The genetic determinants of recurrent somatic mutations in 43,693 blood genomes. - Weinstock, Joshua S; Laurie, Cecelia A; Broome, Jai G; Taylor, Kent D; Guo, Xiuqing; Shuldiner, Alan R; O'Connell, Jeffrey R; Lewis, Joshua P; Boerwinkle, Eric; Barnes, Kathleen C; Chami, Nathalie; Kenny, Eimear E; et al. (Sci Adv, 2023)
Nononcogenic somatic mutations are thought to be uncommon and inconsequential. To test this, we analyzed 43,693 National Heart, Lung and Blood Institute Trans-Omics for Precision Medicine blood whole genomes from 37 cohorts and identified 7131 non-missense somatic mutations that are recurrently mutated in at least 50 individuals. These recurrent non-missense somatic mutations (RNMSMs) are not clearly explained by other clonal phenomena such as clonal hematopoiesis. RNMSM prevalence increased with age, with an average 50-year-old having 27 RNMSMs. Inherited germline variation associated with RNMSM acquisition. These variants were found in genes involved in adaptive immune function, proinflammatory cytokine production, and lymphoid lineage commitment. In addition, the presence of eight specific RNMSMs associated with blood cell traits at effect sizes comparable to Mendelian genetic mutations. Overall, we found that somatic mutations in blood are an unexpectedly common phenomenon with ancestry-specific determinants and human health consequences.
Keywords: Germ-Line Mutation; Hematopoiesis; Humans; Middle Aged; Mutation; Mutation, Missense; Phenotype

Genome-Wide Association Studies and fine-mapping of genomic loci for n-3 and n-6 Polyunsaturated Fatty Acids in Hispanic American and African American Cohorts. - Yang, Chaojie; Veenstra, Jenna; Bartz, Traci; Pahl, Matthew; Hallmark, Brian; Chen, Yii-Der Ida; Westra, Jason; Steffen, Lyn; Brown, Christopher; Siscovick, David; Tsai, Michael; Wood, Alexis; et al. (Res Sq, 2023)
Omega-3 (n-3) and omega-6 (n-6) polyunsaturated fatty acids (PUFAs) play critical roles in human health. Prior genome-wide association studies (GWAS) of n-3 and n-6 PUFAs in European Americans from the CHARGE Consortium have documented strong genetic signals in/near the locus on chromosome 11. We performed a GWAS of four n-3 and four n-6 PUFAs in Hispanic American (n = 1454) and African American (n = 2278) participants from three CHARGE cohorts. Applying a genome-wide significance threshold of  < 5 x 10 , we confirmed association of the signal and found evidence of two additional signals (in and ) within 200 kb of the originally reported signal. Outside of the region, we identified novel signals for arachidonic acid (AA) in Hispanic Americans located in/near genes including , , and spanning a > 9 Mb region on chromosome 11 (57.5Mb ~ 67.1Mb). Among these novel signals, we found associations unique to Hispanic Americans, including rs28364240, a missense variant for AA that is common in CHARGE Hispanic Americans but absent in other race/ancestry groups. Our study sheds light on the genetics of PUFAs and the value of investigating complex trait genetics across diverse ancestry populations.

Genome-Wide Interaction Analysis with DASH Diet Score Identified Novel Loci for Systolic Blood Pressure. - Guirette, Melanie; Lan, Jessie; McKeown, Nicola; Brown, Michael R; Chen, Han; de Vries, Paul S; Kim, Hyunju; Rebholz, Casey M; Morrison, Alanna C; Bartz, Traci M; Fretts, Amanda M; Guo, Xiuqing; et al. (medRxiv, 2023)
OBJECTIVE: We examined interactions between genotype and a Dietary Approaches to Stop Hypertension (DASH) diet score in relation to systolic blood pressure (SBP). METHODS: We analyzed up to 9,420,585 biallelic imputed single nucleotide polymorphisms (SNPs) in up to 127,282 individuals of six population groups (91% of European population) from the Cohorts for Heart and Aging Research in Genomic Epidemiology consortium (CHARGE; n=35,660) and UK Biobank (n=91,622) and performed European population-specific and cross-population meta-analyses. RESULTS: We identified three loci in European-specific analyses and an additional four loci in cross-population analyses at P for interaction < 5e-8. We observed a consistent interaction between rs117878928 at 15q25.1 (minor allele frequency = 0.03) and the DASH diet score (P for interaction = 4e-8; P for heterogeneity = 0.35) in European population, where the interaction effect size was 0.42±0.09 mm Hg (P for interaction = 9.4e-7) and 0.20±0.06 mm Hg (P for interaction = 0.001) in CHARGE and the UK Biobank, respectively. The 1 Mb region surrounding rs117878928 was enriched with -expression quantitative trait loci (eQTL) variants (P = 4e-273) and -DNA methylation quantitative trait loci (mQTL) variants (P = 1e-300). While the closest gene for rs117878928 is , the highest narrow sense heritability accounted by SNPs potentially interacting with the DASH diet score in this locus was for gene at 15q25.1. CONCLUSION: We demonstrated gene-DASH diet score interaction effects on SBP in several loci. Studies with larger diverse populations are needed to validate our findings.

{Identification of circulating proteins associated with general cognitive function among middle-aged and older adults - Tin, A.; Fohner, A. E.; Yang, Q.; Brody, J. A.; Davies, G.; Yao, J.; Liu, D.; Caro, I.; Lindbohm, J. V.; Duggan, M. R.; Meirelles, O.; Harris, S. E.; et al. (Commun Biol, 2023)
2.0E-4). Proteins implicated as causes or consequences of AD susceptibility may provide new insight into the potential relationship between immunity and AD susceptibility as well as potential therapeutic targets.

Late-life plasma proteins associated with prevalent and incident frailty: A proteomic analysis. - Liu, Fangyu; Austin, Thomas R; Schrack, Jennifer A; Chen, Jingsha; Walston, Jeremy; Mathias, Rasika A; Grams, Morgan; Odden, Michelle C; Newman, Anne; Psaty, Bruce M; Ramonfaur, Diego; Shah, Amil M; et al. (Aging Cell, 2023)
Proteomic approaches have unique advantages in the identification of biological pathways that influence physical frailty, a multifactorial geriatric syndrome predictive of adverse health outcomes in older adults. To date, proteomic studies of frailty are scarce, and few evaluated prefrailty as a separate state or examined predictors of incident frailty. Using plasma proteins measured by 4955 SOMAmers in the Atherosclerosis Risk in Community study, we identified 134 and 179 proteins cross-sectionally associated with prefrailty and frailty, respectively, after Bonferroni correction (p < 1 × 10 ) among 3838 older adults aged ≥65 years, adjusting for demographic and physiologic factors and chronic diseases. Among them, 23 (17%) and 82 (46%) were replicated in the Cardiovascular Health Study using the same models (FDR p < 0.05). Notably, higher odds of prefrailty and frailty were observed with higher levels of growth differentiation factor 15 (GDF15; p  = 1 × 10 , p  = 2 × 10 ), transgelin (TAGLN; p  = 2 × 10 , p  = 6 × 10 ), and insulin-like growth factor-binding protein 2 (IGFBP2; p  = 5 × 10 , p  = 1 × 10 ) and with a lower level of growth hormone receptor (GHR, p  = 3 × 10 , p  = 2 × 10 ). Longitudinally, we identified 4 proteins associated with incident frailty (p < 1 × 10 ). Higher levels of triggering receptor expressed on myeloid cells 1 (TREM1), TAGLN, and heart and adipocyte fatty-acid binding proteins predicted incident frailty. Differentially regulated proteins were enriched in pathways and upstream regulators related to lipid metabolism, angiogenesis, inflammation, and cell senescence. Our findings provide a set of plasma proteins and biological mechanisms that were dysregulated in both the prodromal and the clinical stage of frailty, offering new insights into frailty etiology and targets for intervention.

loss-of-function variants: Compatible with longevity and associated with resistance to Alzheimer's Disease pathology - Chemparathy, A.; Guen, Y. L.; Chen, S.; Lee, E. G.; Leong, L.; Gorzynski, J.; Xu, G.; Belloy, M.; Kasireddy, N.; Tauber, A. P.; Williams, K.; Stewart, I.; et al. (medRxiv, 2023)
4 or its protein product as a viable therapeutic option.

Mosaic chromosomal alterations in blood across ancestries using whole-genome sequencing. - Jakubek, Yasminka A; Zhou, Ying; Stilp, Adrienne; Bacon, Jason; Wong, Justin W; Ozcan, Zuhal; Arnett, Donna; Barnes, Kathleen; Bis, Joshua C; Boerwinkle, Eric; Brody, Jennifer A; Carson, April P; et al. (Nat Genet, 2023)
Megabase-scale mosaic chromosomal alterations (mCAs) in blood are prognostic markers for a host of human diseases. Here, to gain a better understanding of mCA rates in genetically diverse populations, we analyzed whole-genome sequencing data from 67,390 individuals from the National Heart, Lung, and Blood Institute Trans-Omics for Precision Medicine program. We observed higher sensitivity with whole-genome sequencing data, compared with array-based data, in uncovering mCAs at low mutant cell fractions and found that individuals of European ancestry have the highest rates of autosomal mCAs and the lowest rates of chromosome X mCAs, compared with individuals of African or Hispanic ancestry. Although further studies in diverse populations will be needed to replicate our findings, we report three loci associated with loss of chromosome X, associations between autosomal mCAs and rare variants in DCPS, ADM17, PPP1R16B and TET2 and ancestry-specific variants in ATM and MPL with mCAs in cis.
Keywords: Black People; Genome, Human; Genome-Wide Association Study; Hispanic or Latino; Humans; Mosaicism; Precision Medicine

Multi-ancestry genome-wide study identifies effector genes and druggable pathways for coronary artery calcification. - Kavousi, Maryam; Bos, Maxime M; Barnes, Hanna J; Lino Cardenas, Christian L; Wong, Doris; Lu, Haojie; Hodonsky, Chani J; Landsmeer, Lennart P L; Turner, Adam W; Kho, Minjung; Hasbani, Natalie R; de Vries, Paul S; et al. (Nat Genet, 2023)
Coronary artery calcification (CAC), a measure of subclinical atherosclerosis, predicts future symptomatic coronary artery disease (CAD). Identifying genetic risk factors for CAC may point to new therapeutic avenues for prevention. Currently, there are only four known risk loci for CAC identified from genome-wide association studies (GWAS) in the general population. Here we conducted the largest multi-ancestry GWAS meta-analysis of CAC to date, which comprised 26,909 individuals of European ancestry and 8,867 individuals of African ancestry. We identified 11 independent risk loci, of which eight were new for CAC and five had not been reported for CAD. These new CAC loci are related to bone mineralization, phosphate catabolism and hormone metabolic pathways. Several new loci harbor candidate causal genes supported by multiple lines of functional evidence and are regulators of smooth muscle cell-mediated calcification ex vivo and in vitro. Together, these findings help refine the genetic architecture of CAC and extend our understanding of the biological and potential druggable pathways underlying CAC.

Multi-ancestry genome-wide study in >2.5 million individuals reveals heterogeneity in mechanistic pathways of type 2 diabetes and complications. - Suzuki, Ken; Hatzikotoulas, Konstantinos; Southam, Lorraine; Taylor, Henry J; Yin, Xianyong; Lorenz, Kim M; Mandla, Ravi; Huerta-Chagoya, Alicia; Rayner, Nigel W; Bocher, Ozvan; Ana Luiza de, S V Arruda; Sonehara, Kyuto; et al. (medRxiv, 2023)
Type 2 diabetes (T2D) is a heterogeneous disease that develops through diverse pathophysiological processes. To characterise the genetic contribution to these processes across ancestry groups, we aggregate genome-wide association study (GWAS) data from 2,535,601 individuals (39.7% non-European ancestry), including 428,452 T2D cases. We identify 1,289 independent association signals at genome-wide significance (P<5×10 ) that map to 611 loci, of which 145 loci are previously unreported. We define eight non-overlapping clusters of T2D signals characterised by distinct profiles of cardiometabolic trait associations. These clusters are differentially enriched for cell-type specific regions of open chromatin, including pancreatic islets, adipocytes, endothelial, and enteroendocrine cells. We build cluster-specific partitioned genetic risk scores (GRS) in an additional 137,559 individuals of diverse ancestry, including 10,159 T2D cases, and test their association with T2D-related vascular outcomes. Cluster-specific partitioned GRS are more strongly associated with coronary artery disease and end-stage diabetic nephropathy than an overall T2D GRS across ancestry groups, highlighting the importance of obesity-related processes in the development of vascular outcomes. Our findings demonstrate the value of integrating multi-ancestry GWAS with single-cell epigenomics to disentangle the aetiological heterogeneity driving the development and progression of T2D, which may offer a route to optimise global access to genetically-informed diabetes care.

Multi-ancestry transcriptome-wide association analyses yield insights into tobacco use biology and drug repurposing. - Chen, Fang; Wang, Xingyan; Jang, Seon-Kyeong; Quach, Bryan C; Weissenkampen, J Dylan; Khunsriraksakul, Chachrit; Yang, Lina; Sauteraud, Renan; Albert, Christine M; Allred, Nicholette D D; Arnett, Donna K; Ashley-Koch, Allison E; et al. (Nat Genet, 2023)
Most transcriptome-wide association studies (TWASs) so far focus on European ancestry and lack diversity. To overcome this limitation, we aggregated genome-wide association study (GWAS) summary statistics, whole-genome sequences and expression quantitative trait locus (eQTL) data from diverse ancestries. We developed a new approach, TESLA (multi-ancestry integrative study using an optimal linear combination of association statistics), to integrate an eQTL dataset with a multi-ancestry GWAS. By exploiting shared phenotypic effects between ancestries and accommodating potential effect heterogeneities, TESLA improves power over other TWAS methods. When applied to tobacco use phenotypes, TESLA identified 273 new genes, up to 55% more compared with alternative TWAS methods. These hits and subsequent fine mapping using TESLA point to target genes with biological relevance. In silico drug-repurposing analyses highlight several drugs with known efficacy, including dextromethorphan and galantamine, and new drugs such as muscle relaxants that may be repurposed for treating nicotine addiction.
Keywords: Biology; Drug Repositioning; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Polymorphism, Single Nucleotide; Tobacco Use; Transcriptome

Multiple Prior Live Births are Associated with Cardiac Remodeling and Heart Failure Risk in Women. - Sarma, Amy A; Paniagua, Samantha M; Lau, Emily S; Wang, Dongyu; Liu, Elizabeth E; Larson, Martin G; Hamburg, Naomi M; Mitchell, Gary F; Kizer, Jorge; Psaty, Bruce M; Allen, Norrina B; Lely, A Titia; et al. (J Card Fail, 2023)
INTRODUCTION: Greater parity has been associated with cardiovascular disease risk, though effects on cardiac remodeling and heart failure risk remain unclear. METHODS: We examined the association of number of live births and echocardiographic measures of cardiac structure and function in participants of the Framingham Heart Study (FHS) using multivariable linear regression. We next examined the association of parity with incident heart failure with preserved (HFpEF) or reduced (HFrEF) ejection fraction using a Fine-Gray subdistribution hazards model in a pooled analysis of n=12,635 participants of FHS, the Cardiovascular Health Study, the Multi-Ethnic Study of Atherosclerosis, and Prevention of Renal and Vascular Endstage Disease. Secondary analyses included major CVD, MI, and stroke. RESULTS: Among n=3931 FHS participants (mean age 48 ± 13 years), higher number of live births was associated with worse LV fractional shortening (multivariable β -1.11 (0.31), p= 0.0005 in ≥ 5 live births vs nulliparous women) and worse cardiac mechanics including global circumferential strain and longitudinal and radial dyssynchrony (p< 0.01 for all comparing ≥ 5 live births vs nulliparity). When examining HF subtypes, women with ≥5 live births were at higher risk of developing future HFrEF compared with nulliparous women (HR 1.93, 95% CI 1.19-3.12, p=0.008); by contrast, a lower risk of HFpEF was observed (HR 0.58, 95% CI 0.37-0.91, p=0.02). CONCLUSIONS: Greater number of live births are associated with worse cardiac structure and function. While there was no association with overall HF, a higher number of live births was associated with greater risk for incident HFrEF.

Plasma Trimethylamine--Oxide and Incident Ischemic Stroke: The Cardiovascular Health Study and the Multi-Ethnic Study of Atherosclerosis. - Lemaitre, Rozenn N; Jensen, Paul N; Wang, Zeneng; Fretts, Amanda M; Sitlani, Colleen M; Nemet, Ina; Sotoodehnia, Nona; de Oliveira Otto, Marcia C; Zhu, Weifei; Budoff, Matt; Longstreth, W T; Psaty, Bruce M; et al. (J Am Heart Assoc, 2023)
Background The association of circulating trimethylamine--oxide (TMAO) with stroke has received limited attention. To address this gap, we examined the associations of serial measures of plasma TMAO with incident ischemic stroke. Methods and Results We used a prospective cohort design with data pooled from 2 cohorts. The settings were the CHS (Cardiovascular Health Study), a cohort of older adults, and the MESA (Multi-Ethnic Study of Atherosclerosis), both in the United States. We measured plasma concentrations of TMAO at baseline and again during the follow-up using high-performance liquid chromatography and mass spectrometry. We assessed the association of plasma TMAO with incident ischemic stroke using proportional hazards regression adjusted for risk factors. The combined cohorts included 11 785 participants without a history of stroke, on average 73 (CHS) and 62 (MESA) years old at baseline, including 60% (CHS) and 53% (MESA) women. We identified 1031 total incident ischemic strokes during a median 15-year follow-up in the combined cohorts. In multivariable analyses, TMAO was significantly associated with incident ischemic stroke risk (hazard ratios comparing a doubling of TMAO: 1.11 [1.03-1.18], =0.004). The association was linear over the range of TMAO concentrations and appeared restricted to those without diagnosed coronary heart disease. An association with hemorrhagic stroke was not found. Conclusions Plasma TMAO levels are associated with incident ischemic stroke in a diverse population. Registration URL: https://www.clinicaltrials.gov. Unique identifier: NCT00005133.
Keywords: Aged; Atherosclerosis; Female; Humans; Ischemic Stroke; Methylamines; Oxides; Prospective Studies; Risk Factors; Stroke; United States

Powerful, scalable and resource-efficient meta-analysis of rare variant associations in large whole genome sequencing studies. - Li, Xihao; Quick, Corbin; Zhou, Hufeng; Gaynor, Sheila M; Liu, Yaowu; Chen, Han; Selvaraj, Margaret Sunitha; Sun, Ryan; Dey, Rounak; Arnett, Donna K; Bielak, Lawrence F; Bis, Joshua C; et al. (Nat Genet, 2023)
Meta-analysis of whole genome sequencing/whole exome sequencing (WGS/WES) studies provides an attractive solution to the problem of collecting large sample sizes for discovering rare variants associated with complex phenotypes. Existing rare variant meta-analysis approaches are not scalable to biobank-scale WGS data. Here we present MetaSTAAR, a powerful and resource-efficient rare variant meta-analysis framework for large-scale WGS/WES studies. MetaSTAAR accounts for relatedness and population structure, can analyze both quantitative and dichotomous traits and boosts the power of rare variant tests by incorporating multiple variant functional annotations. Through meta-analysis of four lipid traits in 30,138 ancestrally diverse samples from 14 studies of the Trans Omics for Precision Medicine (TOPMed) Program, we show that MetaSTAAR performs rare variant meta-analysis at scale and produces results comparable to using pooled data. Additionally, we identified several conditionally significant rare variant associations with lipid traits. We further demonstrate that MetaSTAAR is scalable to biobank-scale cohorts through meta-analysis of TOPMed WGS data and UK Biobank WES data of ~200,000 samples.
Keywords: Exome Sequencing; Genome-Wide Association Study; Lipids; Phenotype; Whole Genome Sequencing

Prediction of Multiple Individual Primary Cardiovascular Events Using Pooled Cohorts. - Sussman, Jeremy B; Whitney, Rachael T; Burke, James F; Hayward, Rodney A; Galecki, Andrzej; Sidney, Stephen; Allen, Norrina Bai; Gottesman, Rebecca F; Heckbert, Susan R; Longstreth, William T; Psaty, Bruce M; Elkind, Mitchell S V; et al. (medRxiv, 2023)
INTRODUCTION: Most current clinical risk prediction scores for cardiovascular disease prevention use a composite outcome. Risk prediction scores for specific cardiovascular events could identify people who are at higher risk for some events than others informing personalized care and trial recruitment. We sought to predict risk for multiple different events, describe how those risks differ, and examine if these differences could improve treatment priorities. METHODS: We used participant-level data from five cohort studies. We included participants between 40 and 79 years old who had no history of myocardial infarction (MI), stroke, or heart failure (HF). We made separate models to predict 10-year rates of first atherosclerotic cardiovascular disease (ASCVD), first fatal or nonfatal MI, first fatal or nonfatal stroke, new-onset HF, fatal ASCVD, fatal MI, fatal stroke, and all-cause mortality using established ASCVD risk factors. To limit overfitting, we used elastic net regularization with alpha = 0.75. We assessed the models for calibration, discrimination, and for correlations between predicted risks for different events. We also estimated the potential impact of varying treatment based on patients who are high risk for some ASCVD events, but not others. RESULTS: Our study included 24,505 people; 55.6% were women, and 20.7% were non-Hispanic Black. Our models had C-statistics between 0.75 for MI and 0.85 for HF, good calibration, and minimal overfitting. The models were least similar for fatal stroke and all MI (0.58). In 1,840 participants whose risk of MI but not stroke or all-cause mortality was in the top quartile, we estimate one blood pressure-lowering medication would have a 2.4% chance of preventing any ASCVD event per 10 years. A moderate-strength statin would have a 2.1% chance. In 1,039 participants who had top quartile risk of stroke but not MI or mortality, a blood pressure-lowering medication would have a 2.5% chance of preventing an event, but a moderate-strength statin, 1.6%. CONCLUSION: We developed risk scores for eight key clinical events and found that cardiovascular risk varies somewhat for different clinical events. Future work could determine if tailoring decisions by risk of separate events can improve care.

Rare variants in long non-coding RNAs are associated with blood lipid levels in the TOPMed Whole Genome Sequencing Study. - Wang, Yuxuan; Selvaraj, Margaret Sunitha; Li, Xihao; Li, Zilin; Holdcraft, Jacob A; Arnett, Donna K; Bis, Joshua C; Blangero, John; Boerwinkle, Eric; Bowden, Donald W; Cade, Brian E; Carlson, Jenna C; et al. (medRxiv, 2023)
Long non-coding RNAs (lncRNAs) are known to perform important regulatory functions. Large-scale whole genome sequencing (WGS) studies and new statistical methods for variant set tests now provide an opportunity to assess the associations between rare variants in lncRNA genes and complex traits across the genome. In this study, we used high-coverage WGS from 66,329 participants of diverse ancestries with blood lipid levels (LDL-C, HDL-C, TC, and TG) in the National Heart, Lung, and Blood Institute (NHLBI) Trans-Omics for Precision Medicine (TOPMed) program to investigate the role of lncRNAs in lipid variability. We aggregated rare variants for 165,375 lncRNA genes based on their genomic locations and conducted rare variant aggregate association tests using the STAAR (variant-Set Test for Association using Annotation infoRmation) framework. We performed STAAR conditional analysis adjusting for common variants in known lipid GWAS loci and rare coding variants in nearby protein coding genes. Our analyses revealed 83 rare lncRNA variant sets significantly associated with blood lipid levels, all of which were located in known lipid GWAS loci (in a ±500 kb window of a Global Lipids Genetics Consortium index variant). Notably, 61 out of 83 signals (73%) were conditionally independent of common regulatory variations and rare protein coding variations at the same loci. We replicated 34 out of 61 (56%) conditionally independent associations using the independent UK Biobank WGS data. Our results expand the genetic architecture of blood lipids to rare variants in lncRNA, implicating new therapeutic opportunities.

A statistical framework for powerful multi-trait rare variant analysis in large-scale whole-genome sequencing studies. - Li, Xihao; Chen, Han; Selvaraj, Margaret Sunitha; Van Buren, Eric; Zhou, Hufeng; Wang, Yuxuan; Sun, Ryan; McCaw, Zachary R; Yu, Zhi; Arnett, Donna K; Bis, Joshua C; Blangero, John; et al. (bioRxiv, 2023)
Large-scale whole-genome sequencing (WGS) studies have improved our understanding of the contributions of coding and noncoding rare variants to complex human traits. Leveraging association effect sizes across multiple traits in WGS rare variant association analysis can improve statistical power over single-trait analysis, and also detect pleiotropic genes and regions. Existing multi-trait methods have limited ability to perform rare variant analysis of large-scale WGS data. We propose MultiSTAAR, a statistical framework and computationally-scalable analytical pipeline for functionally-informed multi-trait rare variant analysis in large-scale WGS studies. MultiSTAAR accounts for relatedness, population structure and correlation among phenotypes by jointly analyzing multiple traits, and further empowers rare variant association analysis by incorporating multiple functional annotations. We applied MultiSTAAR to jointly analyze three lipid traits (low-density lipoprotein cholesterol, high-density lipoprotein cholesterol and triglycerides) in 61,861 multi-ethnic samples from the Trans-Omics for Precision Medicine (TOPMed) Program. We discovered new associations with lipid traits missed by single-trait analysis, including rare variants within an enhancer of and an intergenic region on chromosome 1.

{Structural Variation Detection and Association Analysis of Whole-Genome-Sequence Data from 16,905 Alzheimer's Diseases Sequencing Project Subjects - Wang, H.; Dombroski, B. A.; Cheng, P. L.; Tucci, A.; Si, Y. Q.; Farrell, J. J.; Tzeng, J. Y.; Leung, Y. Y.; Malamon, J. S.; Wang, L. S.; Vardarajan, B. N.; Farrer, L. A.; et al. (medRxiv, 2023)
. We also identified 16 SVs associated with AD and 13 SVs associated with AD-related pathological/cognitive endophenotypes. Our findings demonstrate the broad impact of SVs on AD genetics.\ Alzheimer's disease, Structural variation, Copy number variation.

{Structural Variation Detection and Association Analysis of Whole-Genome-Sequence Data from 16,905 Alzheimer's Diseases Sequencing Project Subjects - Lee, W. P.; Wang, H.; Dombroski, B.; Cheng, P. L.; Tucci, A.; Si, Y. Q.; Farrell, J.; Tzeng, J. Y.; Leung, Y. Y.; Malamon, J.; Wang, L. S.; Vardarajan, B.; et al. (Res Sq, 2023)
. We also identified 16 SVs associated with AD and 13 SVs linked to AD-related pathological/cognitive endophenotypes. This study highlights the pivotal role of SVs in shaping our understanding of AD genetics.

Substitution of self-reported measures for objectively assessed grip strength and slow walk in the Physical Frailty Phenotype: ramifications for validity. - Bandeen-Roche, Karen; Tian, Jing; Buta, Brian; Walston, Jeremy; Xue, Qian-Li (BMC Geriatr, 2023)
BACKGROUND: Frailty assessment promises to identify older adults at risk for adverse consequences following stressors and target interventions to improve health outcomes. The Physical Frailty Phenotype (PFP) is a widely-studied, well validated assessment but incorporates performance-based slow walk and grip strength criteria that challenge its use in some clinical settings. Variants replacing performance-based elements with self-reported proxies have been proposed. Our study evaluated whether commonly available disability self-reports could be substituted for the performance-based criteria in the PFP while still identifying as "frail" the same subpopulations of individuals. METHODS: Parallel analyses were conducted in 3393 female and 2495 male Cardiovascular Health Study, Round 2 participants assessed in 1989-90. Candidate self-reported proxies for the phenotype's "slowness" and "weakness" criteria were evaluated for comparable prevalence and agreement by mode of measurement. For best-performing candidates: Frailty status (3 + positive criteria out of 5) was compared for prevalence and agreement between the PFP and mostly self-reported versions. Personal characteristics were compared between those adjudicated as frail by (a) only a self-reported version; (b) only the PFP; (c) both, using bivariable analyses and multinomial logistic regression. RESULTS: Self-reported difficulty walking ½ mile was selected as a proxy for the phenotype's slowness criterion. Two self-reported weakness proxies were examined: difficulty transferring from a bed or chair or gripping with hands, and difficulty as just defined or in lifting a 10-pound bag. Prevalences matched to within 4% between self-reported and performance-based criteria in the whole sample, but in all cases the self-reported prevalence for women exceeded that for men by 11% or more. Cross-modal agreement was moderate, with by-criterion and frailty-wide Kappa statistics of 0.55-0.60 in all cases. Frail subgroups (a), (b), (c) were independently discriminated (p < 0.05) by race, BMI, and depression in women; by age in men; and by self-reported health for both. CONCLUSIONS: Commonly used self-reported disability items cannot be assumed to stand in for performance-based criteria in the PFP. We found subpopulations identified as frail by resultant phenotypes versus the original phenotype to systematically differ. Work to develop self-reported proxies that more closely replicate their objective phenotypic counterparts than standard disability self-reports is needed.
Keywords: Advance Directives; Female; Frailty; Hand Strength; Humans; Male; Phenotype; Self Report

Time-to-Event Genome-Wide Association Study for Incident Cardiovascular Disease in People with Type 2 Diabetes Mellitus. - Kwak, Soo Heon; Hernandez-Cancela, Ryan B; DiCorpo, Daniel A; Condon, David E; Merino, Jordi; Wu, Peitao; Brody, Jennifer A; Yao, Jie; Guo, Xiuqing; Ahmadizar, Fariba; Meyer, Mariah; Sincan, Murat; et al. (medRxiv, 2023)
BACKGROUND: Type 2 diabetes mellitus (T2D) confers a two- to three-fold increased risk of cardiovascular disease (CVD). However, the mechanisms underlying increased CVD risk among people with T2D are only partially understood. We hypothesized that a genetic association study among people with T2D at risk for developing incident cardiovascular complications could provide insights into molecular genetic aspects underlying CVD. METHODS: From 16 studies of the Cohorts for Heart & Aging Research in Genomic Epidemiology (CHARGE) Consortium, we conducted a multi-ancestry time-to-event genome-wide association study (GWAS) for incident CVD among people with T2D using Cox proportional hazards models. Incident CVD was defined based on a composite of coronary artery disease (CAD), stroke, and cardiovascular death that occurred at least one year after the diagnosis of T2D. Cohort-level estimated effect sizes were combined using inverse variance weighted fixed effects meta-analysis. We also tested 204 known CAD variants for association with incident CVD among patients with T2D. RESULTS: A total of 49,230 participants with T2D were included in the analyses (31,118 European ancestries and 18,112 non-European ancestries) which consisted of 8,956 incident CVD cases over a range of mean follow-up duration between 3.2 and 33.7 years (event rate 18.2%). We identified three novel, distinct genetic loci for incident CVD among individuals with T2D that reached the threshold for genome-wide significance ( <5.0×10 ): rs147138607 (intergenic variant between and ) with a hazard ratio (HR) 1.23, 95% confidence interval (CI) 1.15 - 1.32, =3.6×10 , rs11444867 (intergenic variant near ) with HR 1.89, 95% CI 1.52 - 2.35, =9.9×10 , and rs335407 (intergenic variant between and ) HR 1.25, 95% CI 1.16 - 1.35, =1.5×10 . Among 204 known CAD loci, 32 were associated with incident CVD in people with T2D with <0.05, and 5 were significant after Bonferroni correction ( <0.00024, 0.05/204). A polygenic score of these 204 variants was significantly associated with incident CVD with HR 1.14 (95% CI 1.12 - 1.16) per 1 standard deviation increase ( =1.0×10 ). CONCLUSIONS: The data point to novel and known genomic regions associated with incident CVD among individuals with T2D. CLINICAL PERSPECTIVE: We conducted a large-scale multi-ancestry time-to-event GWAS to identify genetic variants associated with CVD among people with T2D. Three variants were significantly associated with incident CVD in people with T2D: rs147138607 (intergenic variant between and ), rs11444867 (intergenic variant near ), and rs335407 (intergenic variant between and ). A polygenic score composed of known CAD variants identified in the general population was significantly associated with the risk of CVD in people with T2D. There are genetic risk factors specific to T2D that could at least partially explain the excess risk of CVD in people with T2D.In addition, we show that people with T2D have enrichment of known CAD association signals which could also explain the excess risk of CVD.

A Type 1 Diabetes Polygenic Score Is Not Associated With Prevalent Type 2 Diabetes in Large Population Studies. - Srinivasan, Shylaja; Wu, Peitao; Mercader, Josep M; Udler, Miriam S; Porneala, Bianca C; Bartz, Traci M; Floyd, James S; Sitlani, Colleen; Guo, Xiquing; Haessler, Jeffrey; Kooperberg, Charles; Liu, Jun; et al. (J Endocr Soc, 2023)
CONTEXT: Both type 1 diabetes (T1D) and type 2 diabetes (T2D) have significant genetic contributions to risk and understanding their overlap can offer clinical insight. OBJECTIVE: We examined whether a T1D polygenic score (PS) was associated with a diagnosis of T2D in the Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) consortium. METHODS: We constructed a T1D PS using 79 known single nucleotide polymorphisms associated with T1D risk. We analyzed 13 792 T2D cases and 14 169 controls from CHARGE cohorts to determine the association between the T1D PS and T2D prevalence. We validated findings in an independent sample of 2256 T2D cases and 27 052 controls from the Mass General Brigham Biobank (MGB Biobank). As secondary analyses in 5228 T2D cases from CHARGE, we used multivariable regression models to assess the association of the T1D PS with clinical outcomes associated with T1D. RESULTS: The T1D PS was not associated with T2D both in CHARGE ( = .15) and in the MGB Biobank ( = .87). The partitioned human leukocyte antigens only PS was associated with T2D in CHARGE (OR 1.02 per 1 SD increase in PS, 95% CI 1.01-1.03, = .006) but not in the MGB Biobank. The T1D PS was weakly associated with insulin use (OR 1.007, 95% CI 1.001-1.012, = .03) in CHARGE T2D cases but not with other outcomes. CONCLUSION: In large biobank samples, a common variant PS for T1D was not consistently associated with prevalent T2D. However, possible heterogeneity in T2D cannot be ruled out and future studies are needed do subphenotyping.

Type 2 Diabetes Modifies the Association of CAD Genomic Risk Variants With Subclinical Atherosclerosis. - Hasbani, Natalie R; Westerman, Kenneth E; Heon Kwak, Soo; Chen, Han; Li, Xihao; DiCorpo, Daniel; Wessel, Jennifer; Bis, Joshua C; Sarnowski, Chloe; Wu, Peitao; Bielak, Lawrence F; Guo, Xiuqing; et al. (Circ Genom Precis Med, 2023)
BACKGROUND: Individuals with type 2 diabetes (T2D) have an increased risk of coronary artery disease (CAD), but questions remain about the underlying pathology. Identifying which CAD loci are modified by T2D in the development of subclinical atherosclerosis (coronary artery calcification [CAC], carotid intima-media thickness, or carotid plaque) may improve our understanding of the mechanisms leading to the increased CAD in T2D. METHODS: We compared the common and rare variant associations of known CAD loci from the literature on CAC, carotid intima-media thickness, and carotid plaque in up to 29 670 participants, including up to 24 157 normoglycemic controls and 5513 T2D cases leveraging whole-genome sequencing data from the Trans-Omics for Precision Medicine program. We included first-order T2D interaction terms in each model to determine whether CAD loci were modified by T2D. The genetic main and interaction effects were assessed using a joint test to determine whether a CAD variant, or gene-based rare variant set, was associated with the respective subclinical atherosclerosis measures and then further determined whether these loci had a significant interaction test. RESULTS: Using a Bonferroni-corrected significance threshold of <1.6×10, we identified 3 genes (, , and ) associated with CAC and 2 genes ( and ) associated with carotid intima-media thickness and carotid plaque, respectively, through gene-based rare variant set analysis. Both and also had significantly different associations for CAC in T2D cases versus controls. No significant interaction tests were identified through the candidate single-variant analysis. CONCLUSIONS: These results highlight T2D as an important modifier of rare variant associations in CAD loci with CAC.

Vaccination Against Pneumonia May Provide Genotype-Specific Protection Against Alzheimer's Disease. - Ukraintseva, Svetlana; Duan, Matt; Simanek, Amanda M; Holmes, Rachel; Bagley, Olivia; Rajendrakumar, Aravind L; Yashkin, Arseniy P; Akushevich, Igor; Tropsha, Alexander; Whitson, Heather; Yashin, Anatoliy; Arbeev, Konstantin (J Alzheimers Dis, 2023)
Vaccine repurposing that considers individual genotype may aid personalized prevention of Alzheimer's disease (AD). In this retrospective cohort study, we used Cardiovascular Health Study data to estimate associations of pneumococcal polysaccharide vaccine and flu shots received between ages 65-75 with AD onset at age 75 or older, taking into account rs6859 polymorphism in NECTIN2 gene (AD risk factor). Pneumococcal vaccine, and total count of vaccinations against pneumonia and flu, were associated with lower odds of AD in carriers of rs6859 A allele, but not in non-carriers. We conclude that pneumococcal polysaccharide vaccine is a promising candidate for genotype-tailored AD prevention.

Whole genome analysis of plasma fibrinogen reveals population-differentiated genetic regulators with putative liver roles. - Huffman, Jennifer E; Nicolas, Jayna; Hahn, Julie; Heath, Adam S; Raffield, Laura M; Yanek, Lisa R; Brody, Jennifer A; Thibord, Florian; Almasy, Laura; Bartz, Traci M; Bielak, Lawrence F; Bowler, Russell P; et al. (medRxiv, 2023)
UNLABELLED: Genetic studies have identified numerous regions associated with plasma fibrinogen levels in Europeans, yet missing heritability and limited inclusion of non-Europeans necessitates further studies with improved power and sensitivity. Compared with array-based genotyping, whole genome sequencing (WGS) data provides better coverage of the genome and better representation of non-European variants. To better understand the genetic landscape regulating plasma fibrinogen levels, we meta-analyzed WGS data from the NHLBI's Trans-Omics for Precision Medicine (TOPMed) program (n=32,572), with array-based genotype data from the Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) Consortium (n=131,340) imputed to the TOPMed or Haplotype Reference Consortium panel. We identified 18 loci that have not been identified in prior genetic studies of fibrinogen. Of these, four are driven by common variants of small effect with reported MAF at least 10% higher in African populations. Three ( , and signals contain predicted deleterious missense variants. Two loci, and , each harbor two conditionally distinct, non-coding variants. The gene region encoding the protein chain subunits ( ), contains 7 distinct signals, including one novel signal driven by rs28577061, a variant common (MAF=0.180) in African reference panels but extremely rare (MAF=0.008) in Europeans. Through phenome-wide association studies in the VA Million Veteran Program, we found associations between fibrinogen polygenic risk scores and thrombotic and inflammatory disease phenotypes, including an association with gout. Our findings demonstrate the utility of WGS to augment genetic discovery in diverse populations and offer new insights for putative mechanisms of fibrinogen regulation. KEY POINTS: Largest and most diverse genetic study of plasma fibrinogen identifies 54 regions (18 novel), housing 69 conditionally distinct variants (20 novel).Sufficient power achieved to identify signal driven by African population variant.Links to (1) liver enzyme, blood cell and lipid genetic signals, (2) liver regulatory elements, and (3) thrombotic and inflammatory disease.

Whole Genome Analysis of Venous Thromboembolism: the Trans-Omics for Precision Medicine Program. - Seyerle, Amanda A; Laurie, Cecelia A; Coombes, Brandon J; Jain, Deepti; Conomos, Matthew P; Brody, Jennifer; Chen, Ming-Huei; Gogarten, Stephanie M; Beutel, Kathleen M; Gupta, Namrata; Heckbert, Susan R; Jackson, Rebecca D; et al. (Circ Genom Precis Med, 2023)
Background Risk for venous thromboembolism has a strong genetic component. Whole genome sequencingfrom the Trans-Omics for Precision Medicine program allowed us to look for new associations, particularly rare variants missed by standard genome-wide association studies. Methods The 3793 cases and 7834 controls (11.6% of cases were Black, Hispanic/Latino, or Asian American) were analyzed using a single variant approach and an aggregate gene-based approach using our primary filter (included only loss-of-function and missense variants predicted to be deleterious) and our secondary filter (included all missense variants). Results Single variant analyses identified associations at 5 known loci. Aggregate gene-based analyses identified only (odds ratio, 6.2 for carriers of rare variants; =7.4×10) when using our primary filter. Employing our secondary variant filter led to a smaller effect size at (odds ratio, 3.8; =1.6×10), while excluding variants found only in rare isoforms led to a larger one (odds ratio, 7.5). Different filtering strategies improved the signal for 2 other known genes: became significant (minimum =1.8×10 with the secondary filter), while did not (minimum =4.4×10 with minor allele frequency <0.0005). Results were largely the same when restricting the analyses to include only unprovoked cases; however, one novel gene, , became significant (=4.4×10 using all missense variants with minor allele frequency <0.0005). Conclusions Here, we have demonstrated the importance of using multiple variant filtering strategies, as we detected additional genes when filtering variants based on their predicted deleteriousness, frequency, and presence on the most expressed isoforms. Our primary analyses did not identify new candidate loci; thus larger follow-up studies are needed to replicate the novel locus and to identify additional rare variation associated with venous thromboembolism.

Whole genome sequence analysis of apparent treatment resistant hypertension status in participants from the Trans-Omics for Precision Medicine program. - Armstrong, Nicole D; Srinivasasainagendra, Vinodh; Ammous, Farah; Assimes, Themistocles L; Beitelshees, Amber L; Brody, Jennifer; Cade, Brian E; Ida Chen, Yii-Der; Chen, Han; de Vries, Paul S; Floyd, James S; Franceschini, Nora; et al. (Front Genet, 2023)
Apparent treatment-resistant hypertension (aTRH) is characterized by the use of four or more antihypertensive (AHT) classes to achieve blood pressure (BP) control. In the current study, we conducted single-variant and gene-based analyses of aTRH among individuals from 12 Trans-Omics for Precision Medicine cohorts with whole-genome sequencing data. Cases were defined as individuals treated for hypertension (HTN) taking three different AHT classes, with average systolic BP ≥ 140 or diastolic BP ≥ 90 mmHg, or four or more medications regardless of BP ( = 1,705). A normotensive control group was defined as individuals with BP < 140/90 mmHg ( = 22,079), not on AHT medication. A second control group comprised individuals who were treatment responsive on one AHT medication with BP < 140/ 90 mmHg ( = 5,424). Logistic regression with kinship adjustment using the Scalable and Accurate Implementation of Generalized mixed models (SAIGE) was performed, adjusting for age, sex, and genetic ancestry. We assessed variants using SKAT-O in rare-variant analyses. Single-variant and gene-based tests were conducted in a pooled multi-ethnicity stratum, as well as self-reported ethnic/racial strata (European and African American). One variant in the known HTN locus, , was a top finding in the multi-ethnic analysis ( = 8.23E-07) for the normotensive control group [rs12476527, odds ratio (95% confidence interval) = 0.80 (0.74-0.88)]. This variant was replicated in the Vanderbilt University Medical Center's DNA repository data. Aggregate gene-based signals included the genes and . Additional work validating these loci in larger, more diverse populations, is warranted to determine whether these regions influence the pathobiology of aTRH.

WHOLE GENOME SEQUENCING ANALYSIS OF BODY MASS INDEX IDENTIFIES NOVEL AFRICAN ANCESTRY-SPECIFIC RISK ALLELE. - Zhang, Xinruo; Brody, Jennifer A; Graff, Mariaelisa; Highland, Heather M; Chami, Nathalie; Xu, Hanfei; Wang, Zhe; Ferrier, Kendra; Chittoor, Geetha; Josyula, Navya S; Li, Xihao; Li, Zilin; et al. (medRxiv, 2023)
Obesity is a major public health crisis associated with high mortality rates. Previous genome-wide association studies (GWAS) investigating body mass index (BMI) have largely relied on imputed data from European individuals. This study leveraged whole-genome sequencing (WGS) data from 88,873 participants from the Trans-Omics for Precision Medicine (TOPMed) Program, of which 51% were of non-European population groups. We discovered 18 BMI-associated signals ( < 5 × 10 ). Notably, we identified and replicated a novel low frequency single nucleotide polymorphism (SNP) in that was common in individuals of African descent. Using a diverse study population, we further identified two novel secondary signals in known BMI loci and pinpointed two likely causal variants in the and loci. Our work demonstrates the benefits of combining WGS and diverse cohorts in expanding current catalog of variants and genes confer risk for obesity, bringing us one step closer to personalized medicine.

Whole Genome Sequencing Based Analysis of Inflammation Biomarkers in the Trans-Omics for Precision Medicine (TOPMed) Consortium. - Jiang, Min-Zhi; Gaynor, Sheila M; Li, Xihao; Van Buren, Eric; Stilp, Adrienne; Buth, Erin; Wang, Fei Fei; Manansala, Regina; Gogarten, Stephanie M; Li, Zilin; Polfus, Linda M; Salimi, Shabnam; et al. (bioRxiv, 2023)
Inflammation biomarkers can provide valuable insight into the role of inflammatory processes in many diseases and conditions. Sequencing based analyses of such biomarkers can also serve as an exemplar of the genetic architecture of quantitative traits. To evaluate the biological insight, which can be provided by a multi-ancestry, whole-genome based association study, we performed a comprehensive analysis of 21 inflammation biomarkers from up to 38,465 individuals with whole-genome sequencing from the Trans-Omics for Precision Medicine (TOPMed) program. We identified 22 distinct single-variant associations across 6 traits - E-selectin, intercellular adhesion molecule 1, interleukin-6, lipoprotein-associated phospholipase A2 activity and mass, and P-selectin - that remained significant after conditioning on previously identified associations for these inflammatory biomarkers. We further expanded upon known biomarker associations by pairing the single-variant analysis with a rare variant set-based analysis that further identified 19 significant rare variant set-based associations with 5 traits. These signals were distinct from both significant single variant association signals within TOPMed and genetic signals observed in prior studies, demonstrating the complementary value of performing both single and rare variant analyses when analyzing quantitative traits. We also confirm several previously reported signals from semi-quantitative proteomics platforms. Many of these signals demonstrate the extensive allelic heterogeneity and ancestry-differentiated variant-trait associations common for inflammation biomarkers, a characteristic we hypothesize will be increasingly observed with well-powered, large-scale analyses of complex traits.

Whole-Genome Sequencing Analysis of Human Metabolome in Multi-Ethnic Populations. - Feofanova, Elena V; Brown, Michael R; Alkis, Taryn; Manuel, Astrid M; Li, Xihao; Tahir, Usman A; Li, Zilin; Mendez, Kevin M; Kelly, Rachel S; Qi, Qibin; Chen, Han; Larson, Martin G; et al. (Nat Commun, 2023)
Circulating metabolite levels may reflect the state of the human organism in health and disease, however, the genetic architecture of metabolites is not fully understood. We have performed a whole-genome sequencing association analysis of both common and rare variants in up to 11,840 multi-ethnic participants from five studies with up to 1666 circulating metabolites. We have discovered 1985 novel variant-metabolite associations, and validated 761 locus-metabolite associations reported previously. Seventy-nine novel variant-metabolite associations have been replicated, including three genetic loci located on the X chromosome that have demonstrated its involvement in metabolic regulation. Gene-based analysis have provided further support for seven metabolite-replicated loci pairs and their biologically plausible genes. Among those novel replicated variant-metabolite pairs, follow-up analyses have revealed that 26 metabolites have colocalized with 21 tissues, seven metabolite-disease outcome associations have been putatively causal, and 7 metabolites might be regulated by plasma protein levels. Our results have depicted the genetic contribution to circulating metabolite levels, providing additional insights into understanding human disease.
Keywords: Ethnicity; Genome-Wide Association Study; Humans; Metabolome; Polymorphism, Single Nucleotide; Quantitative Trait Loci

A comparative study of structural variant calling in WGS from Alzheimer's disease families. - Malamon, John S; Farrell, John J; Xia, Li Charlie; Dombroski, Beth A; Das, Rueben G; Way, Jessica; Kuzma, Amanda B; Valladares, Otto; Leung, Yuk Yee; Scanlon, Allison J; Lopez, Irving Antonio Barrera; Brehony, Jack; et al. (Life Sci Alliance, 2024)
Detecting structural variants (SVs) in whole-genome sequencing poses significant challenges. We present a protocol for variant calling, merging, genotyping, sensitivity analysis, and laboratory validation for generating a high-quality SV call set in whole-genome sequencing from the Alzheimer's Disease Sequencing Project comprising 578 individuals from 111 families. Employing two complementary pipelines, Scalpel and Parliament, for SV/indel calling, we assessed sensitivity through sample replicates (N = 9) with in silico variant spike-ins. We developed a novel metric, D-score, to evaluate caller specificity for deletions. The accuracy of deletions was evaluated by Sanger sequencing. We generated a high-quality call set of 152,301 deletions of diverse sizes. Sanger sequencing validated 114 of 146 detected deletions (78.1%). Scalpel excelled in accuracy for deletions ≤100 bp, whereas Parliament was optimal for deletions >900 bp. Overall, 83.0% and 72.5% of calls by Scalpel and Parliament were validated, respectively, including all 11 deletions called by both Parliament and Scalpel between 101 and 900 bp. Our flexible protocol successfully generated a high-quality deletion call set and a truth set of Sanger sequencing-validated deletions with precise breakpoints spanning 1-17,000 bp.
Keywords: Alzheimer Disease; Humans; Whole Genome Sequencing

Familial Hypercholesterolemia Variant and Cardiovascular Risk in Individuals With Elevated Cholesterol. - Zhang, Yiyi; Dron, Jacqueline S; Bellows, Brandon K; Khera, Amit V; Liu, Junxiu; Balte, Pallavi P; Oelsner, Elizabeth C; Amr, Sami Samir; Lebo, Matthew S; Nagy, Anna; Peloso, Gina M; Natarajan, Pradeep; et al. (JAMA Cardiol, 2024)
IMPORTANCE: Familial hypercholesterolemia (FH) is a genetic disorder that often results in severely high low-density lipoprotein cholesterol (LDL-C) and high risk of premature coronary heart disease (CHD). However, the impact of FH variants on CHD risk among individuals with moderately elevated LDL-C is not well quantified. OBJECTIVE: To assess CHD risk associated with FH variants among individuals with moderately (130-189 mg/dL) and severely (≥190 mg/dL) elevated LDL-C and to quantify excess CHD deaths attributable to FH variants in US adults. DESIGN, SETTING, AND PARTICIPANTS: A total of 21 426 individuals without preexisting CHD from 6 US cohort studies (Atherosclerosis Risk in Communities study, Coronary Artery Risk Development in Young Adults study, Cardiovascular Health Study, Framingham Heart Study Offspring cohort, Jackson Heart Study, and Multi-Ethnic Study of Atherosclerosis) were included, 63 of whom had an FH variant. Data were collected from 1971 to 2018, and the median (IQR) follow-up was 18 (13-28) years. Data were analyzed from March to May 2023. EXPOSURES: LDL-C, cumulative past LDL-C, FH variant status. MAIN OUTCOMES AND MEASURES: Cox proportional hazards models estimated associations between FH variants and incident CHD. The Cardiovascular Disease Policy Model projected excess CHD deaths associated with FH variants in US adults. RESULTS: Of the 21 426 individuals without preexisting CHD (mean [SD] age 52.1 [15.5] years; 12 041 [56.2%] female), an FH variant was found in 22 individuals with moderately elevated LDL-C (0.3%) and in 33 individuals with severely elevated LDL-C (2.5%). The adjusted hazard ratios for incident CHD comparing those with and without FH variants were 2.9 (95% CI, 1.4-6.0) and 2.6 (95% CI, 1.4-4.9) among individuals with moderately and severely elevated LDL-C, respectively. The association between FH variants and CHD was slightly attenuated when further adjusting for baseline LDL-C level, whereas the association was no longer statistically significant after adjusting for cumulative past LDL-C exposure. Among US adults 20 years and older with no history of CHD and LDL-C 130 mg/dL or higher, more than 417 000 carry an FH variant and were projected to experience more than 12 000 excess CHD deaths in those with moderately elevated LDL-C and 15 000 in those with severely elevated LDL-C compared with individuals without an FH variant. CONCLUSIONS AND RELEVANCE: In this pooled cohort study, the presence of FH variants was associated with a 2-fold higher CHD risk, even when LDL-C was only moderately elevated. The increased CHD risk appeared to be largely explained by the higher cumulative LDL-C exposure in individuals with an FH variant compared to those without. Further research is needed to assess the value of adding genetic testing to traditional phenotypic FH screening.

{A genetic association study of circulating coagulation Factor VIII and von Willebrand Factor levels - de Vries, P. S.; Reventun, P.; Brown, M. R.; Heath, A. S.; Huffman, J. E.; Le, N. Q.; Bebo, A.; Brody, J. A.; Temprano-Sagrera, G.; Raffield, L. M.; Ozel, A. B.; Thibord, F.; et al. (Blood, 2024)
10-9) at seven new loci for FVIII (ST3GAL4, CLEC4M, B3GNT2, ASGR1, F12, KNG1, and TREM1/NCR2) and one for VWF (B3GNT2). VWF, ABO, and STAB2 were associated with FVIII and VWF in gene-based analyses. Multi-phenotype analysis of FVIII and VWF identified another three new loci, including PDIA3. Silencing of B3GNT2 and the previously reported CD36 gene decreased release of FVIII by HLECs, while silencing of B3GNT2, CD36, and PDIA3 decreased release of VWF by HVECs. Mendelian randomization supports causal association of higher FVIII and VWF with increased risk of thrombotic outcomes. Seven new loci were identified for FVIII and one for VWF, with evidence supporting causal associations of FVIII and VWF with thrombotic outcomes. B3GNT2, CD36, and PDIA3 modulate the release of FVIII and/or VWF in vitro.

{Genetic associations with dementia-related proteinopathy: Application of item response theory - Katsumata, Y.; Fardo, D. W.; Shade, L. M. P.; Wu, X.; Karanth, S. D.; Hohman, T. J.; Schneider, J. A.; Bennett, D. A.; Farfel, J. M.; Gauthreaux, K.; Mock, C.; Kukull, W. A.; et al. (Alzheimers Dement, 2024)
Although dementia-related proteinopathy has a strong negative impact on public health, and is highly heritable, understanding of the related genetic architecture is incomplete.\ -synuclein, and TDP-43.\ -synuclein/Lewy bodies. Novel suggestive proteinopathy-linked alleles were also discovered, including several (SDHAF1, TMEM68, and ARHGEF28) with colocalization analyses and/or high degrees of biologic credibility.\ A novel methodology using GPCM enabled insights into gene candidates for driving misfolded proteinopathies.\ Latent factor scores for proteinopathies were estimated using a generalized partial credit model. The three latent continuous scores corresponded well with proteinopathy severity. Novel genes associated with proteinopathies were identified. Several genes had high degrees of biologic credibility for dementia risk factors.

Genetic drivers of heterogeneity in type 2 diabetes pathophysiology. - Suzuki, Ken; Hatzikotoulas, Konstantinos; Southam, Lorraine; Taylor, Henry J; Yin, Xianyong; Lorenz, Kim M; Mandla, Ravi; Huerta-Chagoya, Alicia; Melloni, Giorgio E M; Kanoni, Stavroula; Rayner, Nigel W; Bocher, Ozvan; et al. (Nature, 2024)
Type 2 diabetes (T2D) is a heterogeneous disease that develops through diverse pathophysiological processes and molecular mechanisms that are often specific to cell type. Here, to characterize the genetic contribution to these processes across ancestry groups, we aggregate genome-wide association study data from 2,535,601 individuals (39.7% not of European ancestry), including 428,452 cases of T2D. We identify 1,289 independent association signals at genome-wide significance (P < 5 × 10) that map to 611 loci, of which 145 loci are, to our knowledge, previously unreported. We define eight non-overlapping clusters of T2D signals that are characterized by distinct profiles of cardiometabolic trait associations. These clusters are differentially enriched for cell-type-specific regions of open chromatin, including pancreatic islets, adipocytes, endothelial cells and enteroendocrine cells. We build cluster-specific partitioned polygenic scores in a further 279,552 individuals of diverse ancestry, including 30,288 cases of T2D, and test their association with T2D-related vascular outcomes. Cluster-specific partitioned polygenic scores are associated with coronary artery disease, peripheral artery disease and end-stage diabetic nephropathy across ancestry groups, highlighting the importance of obesity-related processes in the development of vascular outcomes. Our findings show the value of integrating multi-ancestry genome-wide association study data with single-cell epigenomics to disentangle the aetiological heterogeneity that drives the development and progression of T2D. This might offer a route to optimize global access to genetically informed diabetes care.

{Genome-wide association study of preserved ratio impaired spirometry (PRISm) - Higbee, D. H.; Lirio, A.; Hamilton, F.; Granell, R.; Wyss, A. B.; London, S. J.; Bartz, T. M.; Gharib, S. A.; Cho, M. H.; Wan, E.; Silverman, E.; Crapo, J. D.; et al. (Eur Respir J, 2024)
{0.70. PRISm is associated with respiratory symptoms and comorbidities. Our objective was to discover novel genetic signals for PRISm and see if they provide insight into the pathogenesis of PRISm and associated comorbidities.\ We undertook a genome-wide association study (GWAS) of PRISm in UK Biobank participants (Stage 1), and selected single nucleotide polymorphisms (SNPs) reaching genome-wide significance for replication in 13 cohorts (Stage 2). A combined meta-analysis of Stage 1 and Stage 2 was done to determine top SNPs. We used cross-trait linkage disequilibrium score regression to estimate genome-wide genetic correlation between PRISm and pulmonary and extrapulmonary traits. Phenome-wide association studies of top SNPs were performed.\ =0.12

The Gut Microbial Metabolite Trimethylamine N-oxide, Incident CKD, and Kidney Function Decline. - Wang, Meng; Tang, W H Wilson; Li, Xinmin S; de Oliveira Otto, Marcia C; Lee, Yujin; Lemaitre, Rozenn N; Fretts, Amanda; Nemet, Ina; Sotoodehnia, Nona; Sitlani, Colleen M; Budoff, Matthew; DiDonato, Joseph A; et al. (J Am Soc Nephrol, 2024)
BACKGROUND: Trimethylamine N-oxide (TMAO) is a gut microbiota-derived metabolite of dietary phosphatidylcholine and carnitine. Experimentally, TMAO causes kidney injury and tubulointerstitial fibrosis. Little is known about prospective associations between TMAO and kidney outcomes, especially incident CKD. We hypothesized that higher plasma TMAO levels would be associated with higher risk of incident CKD and greater rate of kidney function decline. METHODS: We included 10,564 participants from two community-based, prospective cohorts with estimated glomerular filtration rate (eGFR) ≥ 60 mL/min/1.73m2 to assess incident CKD. TMAO was measured using targeted mass spectrometry at baseline and one follow-up visit. Creatinine and Cystatin C were measured up to 4 times during follow-up and used to compute eGFR. Incident CKD was defined as an eGFR decline ≥ 30% from baseline and a resulting eGFR<60 ml/min/1.73 m2. Time-varying Cox models assessed the association of serial TMAO measures with incident CKD, adjusting for sociodemographic, lifestyle, diet, and cardiovascular disease risk factors. Linear mixed models assessed the association with annualized eGFR change in 10,009 participants with at least one follow-up eGFR measure without exclusions for baseline eGFR levels. RESULTS: During a median follow-up of 9.4 years (interquartile range: 9.1-11.6 years), 979 incident CKD events occurred. Higher TMAO levels associated with higher risk of incident CKD (2nd to 5th vs. 1st quintile HR[95%CI]= 1.65 [1.22-2.23], 1.68 [1.26-2.25], 2.28 [1.72-3.02], and 2.24[1.68-2.98], respectively) and greater annualized eGFR decline ( 2nd to 5th vs. 1st quintile annualized eGFR change= -0.21 [-0.32, -0.09], -0.17 [-0.29, -0.05], -0.35 [-0.47, -0.22], and -0.43[-0.56, -0.30], respectively) with monotonic dose-response relationships. These associations were consistent across different racial/ethnic groups examined. The association with eGFR decline was similar to or larger than that seen for established CKD risk factors including diabetes, per 10 mmHg of higher systolic blood pressure, per 10 years of older age, and Black race. CONCLUSIONS: In community-based US adults, higher serial measures of plasma TMAO were associated with higher risk of incident CKD and greater annualized kidney function decline.

Human whole-exome genotype data for Alzheimer's disease. - Leung, Yuk Yee; Naj, Adam C; Chou, Yi-Fan; Valladares, Otto; Schmidt, Michael; Hamilton-Nelson, Kara; Wheeler, Nicholas; Lin, Honghuang; Gangadharan, Prabhakaran; Qu, Liming; Clark, Kaylyn; Kuzma, Amanda B; et al. (Nat Commun, 2024)
The heterogeneity of the whole-exome sequencing (WES) data generation methods present a challenge to a joint analysis. Here we present a bioinformatics strategy for joint-calling 20,504 WES samples collected across nine studies and sequenced using ten capture kits in fourteen sequencing centers in the Alzheimer's Disease Sequencing Project. The joint-genotype called variant-called format (VCF) file contains only positions within the union of capture kits. The VCF was then processed specifically to account for the batch effects arising from the use of different capture kits from different studies. We identified 8.2 million autosomal variants. 96.82% of the variants are high-quality, and are located in 28,579 Ensembl transcripts. 41% of the variants are intronic and 1.8% of the variants are with CADD > 30, indicating they are of high predicted pathogenicity. Here we show our new strategy can generate high-quality data from processing these diversely generated WES samples. The improved ability to combine data sequenced in different batches benefits the whole genomics research community.
Keywords: Alzheimer Disease; Computational Biology; Data Accuracy; Exome; Genotype; Humans

A Large-Scale Genome-Wide Study of Gene-Sleep Duration Interactions for Blood Pressure in 811,405 Individuals from Diverse Populations. - Nagarajan, Pavithra; Winkler, Thomas W; Bentley, Amy R; Miller, Clint L; Kraja, Aldi T; Schwander, Karen; Lee, Songmi; Wang, Wenyi; Brown, Michael R; Morrison, John L; Giri, Ayush; O'Connell, Jeffrey R; et al. (medRxiv, 2024)
Although both short and long sleep duration are associated with elevated hypertension risk, our understanding of their interplay with biological pathways governing blood pressure remains limited. To address this, we carried out genome-wide cross-population gene-by-short-sleep and long-sleep duration interaction analyses for three blood pressure traits (systolic, diastolic, and pulse pressure) in 811,405 individuals from diverse population groups. We discover 22 novel gene-sleep duration interaction loci for blood pressure, mapped to genes involved in neurological, thyroidal, bone metabolism, and hematopoietic pathways. Non-overlap between short sleep (12) and long sleep (10) interactions underscores the plausibility of distinct influences of both sleep duration extremes in cardiovascular health. With several of our loci reflecting specificity towards population background or sex, our discovery sheds light on the importance of embracing granularity when addressing heterogeneity entangled in gene-environment interactions, and in therapeutic design approaches for blood pressure management.

Multi-omics and pathway analyses of genome-wide associations implicate regulation and immunity in verbal declarative memory performance. - Mei, Hao; Simino, Jeannette; Li, Lianna; Jiang, Fan; Bis, Joshua C; Davies, Gail; Hill, W David; Xia, Charley; Gudnason, Vilmundur; Yang, Qiong; Lahti, Jari; Smith, Jennifer A; et al. (Alzheimers Res Ther, 2024)
BACKGROUND: Uncovering the functional relevance underlying verbal declarative memory (VDM) genome-wide association study (GWAS) results may facilitate the development of interventions to reduce age-related memory decline and dementia. METHODS: We performed multi-omics and pathway enrichment analyses of paragraph (PAR-dr) and word list (WL-dr) delayed recall GWAS from 29,076 older non-demented individuals of European descent. We assessed the relationship between single-variant associations and expression quantitative trait loci (eQTLs) in 44 tissues and methylation quantitative trait loci (meQTLs) in the hippocampus. We determined the relationship between gene associations and transcript levels in 53 tissues, annotation as immune genes, and regulation by transcription factors (TFs) and microRNAs. To identify significant pathways, gene set enrichment was tested in each cohort and meta-analyzed across cohorts. Analyses of differential expression in brain tissues were conducted for pathway component genes. RESULTS: The single-variant associations of VDM showed significant linkage disequilibrium (LD) with eQTLs across all tissues and meQTLs within the hippocampus. Stronger WL-dr gene associations correlated with reduced expression in four brain tissues, including the hippocampus. More robust PAR-dr and/or WL-dr gene associations were intricately linked with immunity and were influenced by 31 TFs and 2 microRNAs. Six pathways, including type I diabetes, exhibited significant associations with both PAR-dr and WL-dr. These pathways included fifteen MHC genes intricately linked to VDM performance, showing diverse expression patterns based on cognitive status in brain tissues. CONCLUSIONS: VDM genetic associations influence expression regulation via eQTLs and meQTLs. The involvement of TFs, microRNAs, MHC genes, and immune-related pathways contributes to VDM performance in older individuals.
Keywords: Aged; Cognition; Genome-Wide Association Study; Humans; Memory; MicroRNAs; Multiomics; Polymorphism, Single Nucleotide

{Multi-trait analysis characterizes the genetics of thyroid function and identifies causal associations with clinical implications - Sterenborg, R. B. T. M.; Steinbrenner, I.; Li, Y.; Bujnis, M. N.; Naito, T.; Marouli, E.; Galesloot, T. E.; Babajide, O.; Andreasen, L.; Astrup, A.; svold, B. O.; Bandinelli, S.; et al. (Nat Commun, 2024)
T3, whereas the FT4 associations represent the thyroid hormone metabolism. Polygenic risk score and Mendelian randomization analyses showed the effects of genetically determined variation in thyroid function on various clinical outcomes, including cardiovascular risk factors and diseases, autoimmune diseases, and cancer. In conclusion, our results improve the understanding of thyroid hormone physiology and highlight the pleiotropic effects of thyroid function on various diseases.

Plasma proteomic signature of human longevity. - Liu, Xiaojuan; Axelsson, Gisli Thor; Newman, Anne B; Psaty, Bruce M; Boudreau, Robert M; Wu, Chenkai; Arnold, Alice M; Aspelund, Thor; Austin, Thomas R; Gardin, Julius M; Siggeirsdottir, Kristin; Tracy, Russell P; et al. (Aging Cell, 2024)
The identification of protein targets that exhibit anti-aging clinical potential could inform interventions to lengthen the human health span. Most previous proteomics research has been focused on chronological age instead of longevity. We leveraged two large population-based prospective cohorts with long follow-ups to evaluate the proteomic signature of longevity defined by survival to 90 years of age. Plasma proteomics was measured using a SOMAscan assay in 3067 participants from the Cardiovascular Health Study (discovery cohort) and 4690 participants from the Age Gene/Environment Susceptibility-Reykjavik Study (replication cohort). Logistic regression identified 211 significant proteins in the CHS cohort using a Bonferroni-adjusted threshold, of which 168 were available in the replication cohort and 105 were replicated (corrected p value <0.05). The most significant proteins were GDF-15 and N-terminal pro-BNP in both cohorts. A parsimonious protein-based prediction model was built using 33 proteins selected by LASSO with 10-fold cross-validation and validated using 27 available proteins in the validation cohort. This protein model outperformed a basic model using traditional factors (demographics, height, weight, and smoking) by improving the AUC from 0.658 to 0.748 in the discovery cohort and from 0.755 to 0.802 in the validation cohort. We also found that the associations of 169 out of 211 proteins were partially mediated by physical and/or cognitive function. These findings could contribute to the identification of biomarkers and pathways of aging and potential therapeutic targets to delay aging and age-related diseases.

A polygenic risk score of atrial fibrillation improves prediction of lifetime risk for heart failure. - Alkis, Taryn; Luo, Xi; Wall, Katherine; Brody, Jennifer; Bartz, Traci; Chang, Patricia P; Norby, Faye L; Hoogeveen, Ron C; Morrison, Alanna C; Ballantyne, Christie M; Coresh, Josef; Boerwinkle, Eric; et al. (ESC Heart Fail, 2024)
AIMS: Heart failure (HF) has shared genetic architecture with its risk factors: atrial fibrillation (AF), body mass index (BMI), coronary heart disease (CHD), systolic blood pressure (SBP), and type 2 diabetes (T2D). We aim to assess the association and risk prediction performance of risk-factor polygenic risk scores (PRSs) for incident HF and its subtypes in bi-racial populations. METHODS AND RESULTS: Five PRSs were constructed for AF, BMI, CHD, SBP, and T2D in White participants of the Atherosclerosis Risk in Communities (ARIC) study. The associations between PRSs and incident HF and its subtypes were assessed using Cox models, and the risk prediction performance of PRSs was assessed using C statistics. Replication was performed in the ARIC study Black and Cardiovascular Health Study (CHS) White participants. In 8624 ARIC study Whites, 1922 (31% cumulative incidence) HF cases developed over 30 years of follow-up. PRSs of AF, BMI, and CHD were associated with incident HF (P < 0.001), where PRS showed the strongest association [hazard ratio (HR): 1.47, 95% confidence interval (CI): 1.41-1.53]. Only the addition of PRS to the ARIC study HF risk equation improved C statistics for 10 year risk prediction from 0.812 to 0.829 (∆C: 0.017, 95% CI: 0.009-0.026). The PRS was associated with both incident HF with reduced ejection fraction (HR: 1.43, 95% CI: 1.27-1.60) and incident HF with preserved ejection fraction (HR: 1.46, 95% CI: 1.33-1.62). The associations between PRS and incident HF and its subtypes, as well as the improved risk prediction, were replicated in the ARIC study Blacks and the CHS Whites (P < 0.050). Protein analyses revealed that N-terminal pro-brain natriuretic peptide and other 98 proteins were associated with PRS . CONCLUSIONS: The PRS was associated with incident HF and its subtypes and had significant incremental value over an established HF risk prediction equation.

Role of Polyunsaturated Fat in Modifying Cardiovascular Risk Associated With Family History of Cardiovascular Disease: Pooled De Novo Results From 15 Observational Studies. - Laguzzi, Federica; Åkesson, Agneta; Marklund, Matti; Qian, Frank; Gigante, Bruna; Bartz, Traci M; Bassett, Julie K; Birukov, Anna; Campos, Hannia; Hirakawa, Yoichiro; Imamura, Fumiaki; Jäger, Susanne; et al. (Circulation, 2024)
BACKGROUND: It is unknown whether dietary intake of polyunsaturated fatty acids (PUFA) modifies the cardiovascular disease (CVD) risk associated with a family history of CVD. We assessed interactions between biomarkers of low PUFA intake and a family history in relation to long-term CVD risk in a large consortium. METHODS: Blood and tissue PUFA data from 40 885 CVD-free adults were assessed. PUFA levels ≤25th percentile were considered to reflect low intake of linoleic, alpha-linolenic, and eicosapentaenoic/docosahexaenoic acids (EPA/DHA). Family history was defined as having ≥1 first-degree relative who experienced a CVD event. Relative risks with 95% CI of CVD were estimated using Cox regression and meta-analyzed. Interactions were assessed by analyzing product terms and calculating relative excess risk due to interaction. RESULTS: After multivariable adjustments, a significant interaction between low EPA/DHA and family history was observed (product term pooled RR, 1.09 [95% CI, 1.02-1.16]; =0.01). The pooled relative risk of CVD associated with the combined exposure to low EPA/DHA, and family history was 1.41 (95% CI, 1.30-1.54), whereas it was 1.25 (95% CI, 1.16-1.33) for family history alone and 1.06 (95% CI, 0.98-1.14) for EPA/DHA alone, compared with those with neither exposure. The relative excess risk due to interaction results indicated no interactions. CONCLUSIONS: A significant interaction between biomarkers of low EPA/DHA intake, but not the other PUFA, and a family history was observed. This novel finding might suggest a need to emphasize the benefit of consuming oily fish for individuals with a family history of CVD.
Keywords: Animals; Biomarkers; Cardiovascular Diseases; Docosahexaenoic Acids; Fatty Acids, Omega-3; Risk Factors

Trajectory of Cognitive Function After Incident Heart Failure. - Shore, Supriya; Li, Hanyu; Zhang, Min; Whitney, Rachael; Gross, Alden L; Bhatt, Ankeet S; Nallamothu, Brahmajee K; Giordani, Bruno; Briceño, Emily M; Sussman, Jeremy B; Gutierrez, Jose; Yaffe, Kristine; et al. (medRxiv, 2024)
BACKGROUND: The size/magnitude of cognitive changes after incident heart failure (HF) are unclear. We assessed whether incident HF is associated with changes in cognitive function after accounting for pre-HF cognitive trajectories and known determinants of cognition. METHODS: This pooled cohort study included adults without HF, stroke, or dementia from six US population-based cohort studies from 1971-2019: Atherosclerosis Risk in Communities Study, Coronary Artery Risk Development in Young Adults Study, Cardiovascular Health Study, Framingham Offspring Study, Multi-Ethnic Study of Atherosclerosis, and Northern Manhattan Study. Linear mixed-effects models estimated changes in cognition at the time of HF (change in the intercept) and the rate of cognitive change over the years after HF (change in the slope), controlling for pre-HF cognitive trajectories and participant factors. Change in global cognition was the primary outcome. Change in executive function and memory were secondary outcomes. Cognitive outcomes were standardized to a -score metric (mean [SD], 50 [10]); a 1-point difference represented a 0.1-SD difference in cognition. RESULTS: The study included 29,614 adults (mean [SD] age was 61.1 [10.5] years, 55% female, 70.3% White, 22.2% Black 7.5% Hispanic). During a median follow-up of 6.6 (Q1-Q3: 5-19.8) years, 1,407 (4.7%) adults developed incident HF. Incident HF was associated with an acute decrease in global cognition (-1.08 points; 95% CI -1.36, -0.80) and executive function (-0.65 points; 95% CI -0.96, -0.34) but not memory (-0.51 points; 95% CI -1.37, 0.35) at the time of the event. Greater acute decreases in global cognition after HF were seen in those with older age, female sex and White race. Individuals with incident HF, compared to HF-free individuals, demonstrated faster declines in global cognition (-0.15 points per year; 95% CI, -0.21, -0.09) and executive function (-0.16 points per year; 95% CI -0.23, -0.09) but not memory ( -0.11 points per year; 95% CI -0.26, 0.04) compared with pre-HF slopes. CONCLUSIONS: In this pooled cohort study, incident HF was associated with an acute decrease in global cognition and executive function at the time of the event and faster declines in global cognition and executive function over the following years.

X-chromosome and kidney function: evidence from a multi-trait genetic analysis of 908,697 individuals reveals sex-specific and sex-differential findings in genes regulated by androgen response elements. - Scholz, Markus; Horn, Katrin; Pott, Janne; Wuttke, Matthias; Kühnapfel, Andreas; Nasr, M Kamal; Kirsten, Holger; Li, Yong; Hoppmann, Anselm; Gorski, Mathias; Ghasemi, Sahar; Li, Man; et al. (Nat Commun, 2024)
X-chromosomal genetic variants are understudied but can yield valuable insights into sexually dimorphic human traits and diseases. We performed a sex-stratified cross-ancestry X-chromosome-wide association meta-analysis of seven kidney-related traits (n = 908,697), identifying 23 loci genome-wide significantly associated with two of the traits: 7 for uric acid and 16 for estimated glomerular filtration rate (eGFR), including four novel eGFR loci containing the functionally plausible prioritized genes ACSL4, CLDN2, TSPAN6 and the female-specific DRP2. Further, we identified five novel sex-interactions, comprising male-specific effects at FAM9B and AR/EDA2R, and three sex-differential findings with larger genetic effect sizes in males at DCAF12L1 and MST4 and larger effect sizes in females at HPRT1. All prioritized genes in loci showing significant sex-interactions were located next to androgen response elements (ARE). Five ARE genes showed sex-differential expressions. This study contributes new insights into sex-dimorphisms of kidney traits along with new prioritized gene targets for further molecular research.
Keywords: Androgens; Chromosomes, Human, X; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Kidney; Male; Polymorphism, Single Nucleotide; Response Elements; Tetraspanins